Are coffee silverskin extracts safe for topical use? An in vitro and in vivo approach - Rodrigues, F.; Pereira, C.; Pimentel, F. B.; Alves, R. C.; Ferreira, M.; Sarmento, B.; Helena Amaral, M.; Oliveira, M. Beatriz P. P. (Industrial Crops and Products, 2015)

Coffee silverskin: A possible valuable cosmetic ingredient - Rodrigues, Francisca; Palmeira-de-Oliveira, Ana; das Neves, Jose; Sarmento, Bruno; Helena Amaral, M.; Oliveira, M. Beatriz P. P. (Pharmaceutical Biology, 2015)

Combined C4d and CD3 immunostaining predicts immunoglobulin (Ig)A nephropathy progression - Faria, B.; Henriques, C.; Matos, A. C.; Daha, M. R.; Pestana, M.; Seelen, M. (Clinical and Experimental Immunology, 2015)

Cortical and trabecular bone in pediatric end-stage kidney disease - Carvalho, Catarina G.; Pereira, Renata C.; Gales, Barbara; Salusky, Isidro B.; Wesseling-Perry, Katherine (Pediatric Nephrology, 2015)

Rehab@home: a tool for home-based motor function rehabilitation - Faria, Carlos; Silva, Jorge; Campilho, Aurelio (Disability and rehabilitation. Assistive technology, 2015)

Safety and toxicity concerns of orally delivered nanoparticles as drug carriers - Araujo, Francisca; Shrestha, Neha; Granja, Pedro L.; Hirvonen, Jouni; Santos, Helder A.; Sarmento, Bruno (Expert opinion on drug metabolism & toxicology, 2015)

Study of paraffin-embedded colon cancer tissue using terahertz spectroscopy - Wahaia, Faustino; Kasalynas, Irmantas; Seliuta, Dalius; Molis, Gediminas; Urbanowicz, Andrzej; Carvalho Silva, Catia D.; Carneiro, Fatima; Valusis, Gintaras; Granja, Pedro L. (Journal of Molecular Structure, 2015)

Terahertz spectroscopy for the study of paraffin-embedded gastric cancer samples - Wahaia, Faustino; Kasalynas, Irmantas; Seliuta, Dalius; Molis, Gediminas; Urbanowicz, Andrzej; Silva, Catia D. Carvalho; Carneiro, Fatima; Valusis, Gintaras; Granja, Pedro L. (Journal of Molecular Structure, 2015)

Actively targeted cetuximab conjugated γ-poly(glutamic acid)-docetaxel nanomedicines for epidermal growth factor receptor over expressing colon cancer cells - Maya, S.; Sarmento, B.; Lakshmanan, V.-K.; Menon, D.; Jayakumar, R. (Journal of Biomedical Nanotechnology, 2014)
Receptor targeted therapy is advantageous in overcoming the toxicity burden of conventional cancer chemotherapeutics. Over expression of epidermal growth factor receptor (EGFR) on cancer cells and its role in metastasis, malignancy and drug resistance in many human cancers lead to its selection as a promising target for cancer treatment. The present work investigated the preparation and characterization of docetaxel (DTXL) loaded γ-poly (glutamic acid) (γ-PGA) nanoparticles (Nps) conjugated with EGFR antibody (Cetuximab, CET) targeted to colon cancer cells (HT-29), highly over expressing EGFR. The flow cytometric analysis revealed two fold increased cellular uptake of CET-DTXL-γ-PGA Nps by HT-29 (EGFR +ve) cells compared to that of IEC-6 (EGFR-ve) cells confirming the active targeting. Cytotoxicity assays (MTT and LDH) showed superior anti-proliferative activity of CET-DTXL-γ-PGA NPs over DTXL-γ-PGA Nps against HT-29 cells. The cell cycle analysis indicated that CET-DTXL-γ-PGA NPs induced cell death in enhanced percentage of HT-29 cells by undergoing cell cycle arrest in G2/M phase compared to that of DTXL-γ-PGA Nps. The mechanism of cancer cell death was analyzed via apoptotic and mitochondrial membrane potential assays and showed that targeted Nps treatment reduced the mitochondrial membrane potential thereby inducing enhanced HT-29 cell death (apoptosis and necrosis). The biodistribution of targeted and non-targeted Nps were analyzed in vivo in Swiss albino mice using NIR imaging. ICG-CET-DTXL-γ-PGA Nps (targeted) and ICG-DTXL-γ-PGA Nps (non-targeted) followed the similar biodistribution pattern in vivo, but with different elimination time. In short, CET-DTXL-γ-PGA nanoparticles enhance the tumor selective therapeutic efficacy for colon cancer. Copyright © 2014 American Scientific Publishers All rights reserved.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: Cetuximab; colon cancer; Docetaxel; Epidermal growth factor receptor; Poly(γ-glutamic acid) nanoparticles; Targeted nanomedicines

Age-period-cohort effects in the incidence of hip fractures: Political and economic events are coincident with changes in risk - Alves, S.M.; Castiglione, D.; Oliveira, C.M.; de Sousa, B.; Pina, M.F. (Osteoporosis International, 2014)
Summary: An age-period cohort model was fitted to analyse time effects on hip fracture incidence rates by sex (Portugal, 2000-2008). Rates increased exponentially with age (age effect). Incidence rates decreased after 2004 for women and were random for men (period effect). New but comprehensive fluctuations in risk were coincident with major political/economic changes (cohort effect). Introduction: Healthcare improvements have allowed prevention but have also increased life expectancy, resulting in more people being at risk. Our aim was to analyse the separate effects of age, period and cohort on incidence rates by sex in Portugal, 2000-2008. Methods: From the National Hospital Discharge Register, we selected admissions (aged ≥49 years) with hip fractures (ICD9-CM, codes 820.x) caused by low/moderate trauma (falls from standing height or less), readmissions and bone cancer cases. We calculated person-years at risk using population data from Statistics Portugal. To identify period and cohort effects for all ages, we used an age-period-cohort model (1-year intervals) followed by generalised additive models with a negative binomial distribution of the observed incidence rates of hip fractures. Results: There were 77,083 hospital admissions (77.4% women). Incidence rates increased exponentially with age for both sexes (age effect). Incidence rates fell after 2004 for women and were random for men (period effect). There was a general cohort effect similar in both sexes; risk of hip fracture altered from an increasing trend for those born before 1930 to a decreasing trend following that year. Risk alterations (not statistically significant) coincident with major political and economic change in the history of Portugal were observed around birth cohorts 1920 (stable-increasing), 1940 (decreasing-increasing) and 1950 (increasing-decreasing only among women). Conclusions: Hip fracture risk was higher for those born during major economically/politically unstable periods. Although bone quality reflects lifetime exposure, conditions at birthmay determine future risk for hip fractures. © International Osteoporosis Foundation and National Osteoporosis Foundation 2013.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: Age-period-cohort; Hip fractures; Osteoporosis; Population-based study; Time trend

Antihyperglycemic Potential of Incretins Orally Delivered via Nano and Microsystems and Subsequent Glucoregulatory Effects - Araujo, Francisca; Shrestha, Neha; Granja, Pedro L.; Hirvonen, Jouni; Santos, Helder A.; Sarmento, Bruno (Current Pharmaceutical Biotechnology, 2014)

Atomic force microscopy measurements reveal multiple bonds between Helicobacter pylori blood group antigen binding adhesin and Lewis b ligand - Parreira, P.; Shi, Q.; Magalhaes, A.; Reis, C.A.; Bugaytsova, J.; Boren, T.; Leckband, D.; Martins, M.C.L. (Journal of the Royal Society, Interface / the Royal Society, 2014)

A biocomposite of collagen nanofibers and nanohydroxyapatite for bone regeneration - Ribeiro, Nilza; Sousa, Susana R.; van Blitterswijk, Clemens A.; Moroni, Lorenzo; Monteiro, Fernando J. (Biofabrication, 2014)

Biodistribution and pharmacokinetics of Dapivirine-loaded nanoparticles after vaginal delivery in mice - Das Neves, J.; Araújo, F.; Andrade, F.; Amiji, M.; Bahia, M.F.; Sarmento, B. (Pharmaceutical Research, 2014)
Purpose: To assess the potential of polymeric nanoparticles (NPs) to affect the genital distribution and local and systemic pharmacokinetics (PK) of the anti-HIV microbicide drug candidate dapivirine after vaginal delivery. Methods: Dapivirine-loaded, poly(ethylene oxide)-coated poly(epsilon-caprolactone) (PEO-PCL) NPs were prepared by a nanoprecipitation method. Genital distribution of NPs and their ability to modify the PK of dapivirine up to 24 h was assessed after vaginal instillation in a female mouse model. Also, the safety of NPs upon daily administration for 14 days was assessed by histological analysis and chemokine/cytokine content in vaginal lavages. Results: PEO-PCL NPs (180-200 nm) were rapidly eliminated after administration but able to distribute throughout the vagina and lower uterus, and capable of tackling mucus and penetrate the epithelial lining. Nanocarriers modified the PK of dapivirine, with higher drug levels being recovered from vaginal lavages and vaginal/lower uterine tissues as compared to a drug suspension. Systemic drug exposure was reduced when NPs were used. Also, NPs were shown safe upon administration for 14 days. Conclusions: Dapivirine-loaded PEO-PCL NPs were able to provide likely favorable genital drug levels, thus attesting the potential value of using this vaginal drug delivery nanosystem in the context of HIV prophylaxis. © 2014 Springer Science+Business Media New York.
Cited By (since 1996):2Export Date: 21 November 2014
Keywords: HIV/AIDS; microbicides; poly(ε-caprolactone); pre-exposure prophylaxis; vaginal drug delivery

Can artificial neural networks be used to predict the origin of ozone episodes? - Fontes, T.; Silva, L.M.; Silva, M. P.; Barros, N.; Carvalho, A. C. (Science of the Total Environment, 2014)
Tropospheric ozone is a secondary pollutant having a negative impact on health and environment. To control and minimize such impact the European Community established regulations to promote a clean air all over Europe. However, when an episode is related with natural mechanisms as Stratosphere-Troposphere Exchanges (STE), the benefits of an action plan to minimize precursor emissions are inefficient. Therefore, this work aims to develop a tool to identify the sources of ozone episodes in order to minimize misclassification and thus avoid the implementation of inappropriate air quality plans. For this purpose, an artificial neural network model - the Multilayer Perceptron - is used as a binary classifier of the source of an ozone episode. Long data series, between 2001 and 2010, considering the ozone precursors, 7Be activity and meteorological conditions were used. With this model, 2-7% of a mean error was achieved, which is considered as a good generalization. Accuracy measures for imbalanced data are also discussed. The MCC values show a good performance of the model (0.65-0.92). Precision and F1-measure indicate that the model specifies a little better the rare class. Thus, the results demonstrate that such a tool can be used to help authorities in the management of ozone, namely when its thresholds are exceeded due natural causes, as the above mentioned STE. Therefore, the resources used to implement an action plan to minimize ozone precursors could be better managed avoiding the implementation of inappropriate measures. © 2014 Elsevier B.V.
Keywords: artificial neural network; Classification; Human health; Ozone; Stratosphere; Troposphere

Cellular strategies to promote vascularisation in tissue engineering applications - Costa-Almeida, R.; Granja, P.L.; Soares, R.; Guerreiro, S.G. (European Cells and Materials, 2014)
Vascularisation is considered to be one of the greatest challenges in tissue engineering. Different strategies exist but cell-based approaches have emerged as a promising therapy to achieve successful vascularisation. The use of endothelial cells to engineer vascularised tissues has been extensively investigated. This field of research has evolved with the discovery of endothelial progenitor cells, a subpopulation with a high regenerative potential. However, the survival of endothelial cell populations alone seems to be impaired. To overcome this problem, co-culture systems, involving supporting cells, like mural cells, fibroblasts, or more tissue-specific cells have been developed. Endothelial cells benefit from the extracellular matrix components and growth factors produced by the supporting cells, which results in neovessel stabilisation and maturation. The use of endothelial progenitor cells in co-culture systems appears to be a promising strategy to promote vascularisation in approaches of increasing complexity. Herein, the authors provide an overview of the cellular strategies that can be used for increasing vascularisation in tissue engineering and regeneration.
Keywords: angiogenesis; Cellular therapies; Co-culture models; Endothelial progenitor cells; Regeneration

Chitosan cross-linked docetaxel loaded EGF receptor targeted nanoparticles for lung cancer cells - Maya, S.; Sarmento, B.; Lakshmanan, V.-K.; Menon, D.; Seabra, V.; Jayakumar, R. (International Journal of Biological Macromolecules, 2014)
Lung cancer, associated with the up-regulated epidermal growth factor receptor (EGFR) led to the development of EGFR targeted anticancer therapeutics. The biopolymeric nanoparticles form an outstanding system for the targeted delivery of therapeutic agents. The present work evaluated the in vitro effects of chitosan cross-linked γ-poly(glutamic acid) (γ-PGA) nanoparticles (Nps) loaded with docetaxel (DTXL) and decorated with Cetuximab (CET), targeted to EGFR over-expressing non-small-cell-lung-cancer (NSCLC) cells (A549). CET-DTXL-γ-PGA Nps was prepared by ionic gelation and CET conjugation via EDC/NHS chemistry. EGFR specificity of targeted Nps was confirmed by the higher uptake rates of EGFR +ve A549 cells compared to that of EGFR -ve cells (NIH3T3). The cytotoxicity of Nps quantified using cell based (MTT/LDH) and flowcytometry (Cell-cycle analysis, Annexin V/PI and JC-1) assays showed superior antiproliferative activity of CET-DTXL-γ-PGA Nps over DTXL-γ-PGA Nps. The A549 cells treated with CET-DTXL-γ-PGA NPs underwent a G2/M phase cell cycle arrest followed by reduction in mitochondrial membrane potential of A549 cells, inducing apoptosis and necrosis resulting in enhanced cancer cell death. CET-DTXL-γ-PGA Nps exhibited enhanced cellular internalization and therapeutic activity, by actively targeting EGFR on NSCLC cells and hence could be an effective alternative to non-specific, conventional chemotherapy by increasing its efficiency by many folds. © 2014 Elsevier B.V.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: Cetuximab; chitosan; Epidermal growth factor receptor; Poly(γ-glutamic acid) nanoparticles; Targeted nanoparticles

Chitosan-modified porous silicon microparticles for enhanced permeability of insulin across intestinal cell monolayers - Shrestha, N.; Shahbazi, M.-A.; Araújo, F.; Zhang, H.; Mäkilä, E.M.; Kauppila, J.; Sarmento, B.; Salonen, J.J.; Hirvonen, J.T.; Santos, H.A. (Biomaterials, 2014)
Porous silicon (PSi) based particulate systems are emerging as an important drug delivery system due to its advantageous properties such as biocompatibility, biodegradability and ability to tailor the particles' physicochemical properties. Here, annealed thermally hydrocarbonized PSi (AnnTHCPSi) and undecylenic acid modified AnnTHCPSi (AnnUnTHCPSi) microparticles were developed as a PSi-based platform for oral delivery of insulin. Chitosan (CS) was used to modify the AnnUnTHCPSi microparticles to enhance the intestinal permeation of insulin. Surface modification with CS led to significant increase in the interaction of PSi microparticles with Caco-2/HT-29 cell co-culture monolayers. Compared to pure insulin, the CS-conjugated microparticles significantly improved the permeation of insulin across the Caco-2/HT-29 cell monolayers, with ca. 20-fold increase in the amount of insulin permeated and ca. 7-fold increase in the apparent permeability (Papp) value. Moreover, among all the investigated particles, the CS-conjugated microparticles also showed the highest amount of insulin associated with the mucus layer and the intestinal Caco-2 cells and mucus secreting HT-29 cells. Our results demonstrate that CS-conjugated AnnUnTHCPSi microparticles can efficiently enhance the insulin absorption across intestinal cells, and thus, they are promising microsystems for the oral delivery of proteins and peptides across the intestinal cell membrane. © 2014 Elsevier Ltd.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: Cell monolayers; chitosan; Diabetes; Insulin; Microparticles; Porous silicon

Co-association of methotrexate and SPIONs into anti-CD64 antibody-conjugated PLGA nanoparticles for theranostic application - Moura, Catarina Costa; Segundo, Marcela A.; das Neves, Jose; Reis, Salette; Sarmento, Bruno (International Journal of Nanomedicine, 2014)

Collagen surface modified poly(ε-caprolactone) scaffolds with improved hydrophilicity and cell adhesion properties - Sousa, I.; Mendes, A.; Pereira, R.F.; Bártolo, P.J. (Materials Letters, 2014)
Poly(ε-caprolactone) (PCL)/collagen scaffolds were produced using a four-step procedure comprising (i) the fabrication of PCL scaffolds through an additive bioextrusion system, (ii) the PCL surface modification using a plasma treatment, (iii) the acrylic acid (AAc) grafting by ultraviolet (UV) polymerization, and (iv) the immobilization of collagen into the scaffold surface through the carbodiimide chemistry. This procedure allowed the quick fabrication of highly porous scaffolds with interconnected pores, well-defined internal architecture and improved cell adhesion properties. The immobilization of collagen into the PCL surface led to a significant enhancement in the hydrophilicity, while the biological tests showed a further improvement in the adhesion of fibroblast cells. These results indicate that the collagen surface modification is an effective strategy to render the hydrophobic nature of PCL and overcome the limited cell interaction of 3D PCL scaffolds. © 2014 Elsevier B.V.
Keywords: BioExtruder; Collagen; poly(ε-caprolactone); Scaffold; Surface modification

Complexity-loss in fetal heart rate dynamics during labor as a potential biomarker of acidemia - Costa, Madalena D.; Schnettler, William T.; Amorim-Costa, Celia; Bernardes, Joao; Costa, Antonia; Goldberger, Ary L.; Ayres-de-Campos, Diogo (Early Human Development, 2014)

Crucial CD8+ T-lymphocyte cytotoxic role in amphotericin B nanospheres efficacy against experimental visceral leishmaniasis - Costa Lima, S.A.; Silvestre, R.; Barros, D.; Cunha, J.; Baltazar, M.T.; Dinis-Oliveira, R.J.; Cordeiro-da-Silva, A. (Nanomedicine: Nanotechnology, Biology, and Medicine, 2014)
This work aims to develop poly(d,l-lactide-co-glycolide) (PLGA)-nanospheres containing amphotericin B (AmB) with suitable physicochemical properties and anti-parasitic activity for visceral leishmaniasis (VL) therapy. When compared with unloaded-PLGA-nanospheres, the AmB-loaded PLGA-nanospheres displayed an increased particle size without affecting the polydispersity and its negative surface charge. AmB stability in the PLGA-nanospheres was >90% over 60-days at 30°C. The AmB-PLGA-nanospheres demonstrated significant in vitro and in vivo efficacy and preferential accumulation in the visceral organs. In addition, an immune-modulatory effect was observed in mice treated with AmB-PLGA-nanospheres, correlating with improved treatment efficacy. The in vitro cytotoxic response of the T-lymphocytes revealed that AmB-PLGA-nanospheres efficacy against VL infection was strictly due to the action of CD8+- but not CD4+-T lymphocytes. Overall, we demonstrate a crucial role for CD8+ cytotoxic T lymphocytes in the efficacy of AmB-PLGA nanospheres, which could represent a potent and affordable alternative for VL therapy. From the Clinical Editor: This study demonstrates a crucial role for CD8+ T lymphocytes in eliminating visceral leishmaniasis in a murine model by enhancing the cytotoxic efficacy of CD8+ T-cells via amphotericin-B-PLGA nanospheres, paving a way to a unique, potentially more potent and cost-effective therapeutic strategy. © 2014 Elsevier Inc.
Keywords: Amphotericin B; Immune-modulation; Poly(d,l-lactide-co-glycolide) nanospheres; Visceral leishmaniasis

Development and evaluation of an algorithm for computer analysis of maternal heart rate during labor - Pinto, P.; Bernardes, J.; Costa-Santos, C.; Amorim-Costa, C.; Silva, M.; Ayres-de-Campos, D. (Computers in Biology and Medicine, 2014)
Background: Maternal heart rate (MHR) recordings are morphologically similar and sometimes coincident with fetal heart rate (FHR) recordings and may be useful for maternal-fetal monitoring if appropriately interpreted. However, similarly to FHR, visual interpretation of MHR features may be poorly reproducible. Methods: A computer algorithm for on-line MHR analysis was developed based on a previously existing version for FHR analysis. Inter-observer and computer-observer agreement and reliability were assessed in 40 one-hour recordings obtained from 20 women during the last 2. h of labor. Agreement and reliability were evaluated for the detection of basal MHR, long-term variability (LTV), accelerations and decelerations, using proportions of agreement (PA) and Kappa statistic (K), with 95% confidence intervals (95% CI). Changes in MHR characteristics between the first and the second hour of the tracings were also evaluated. Results: There was a statistically significant inter-observer and computer-observer agreement and reliability in estimation of basal MHR, accelerations, decelerations and LTV, with PA values ranging from 0.72 (95% CI: 0.62-0.79) to 1.00 (95% CI: 0.99-1.00), and K values ranging from 0.44 (95% CI: 0.28-0.60) to 0.89 (95% CI: 0.82-0.96). Moreover, basal MHR, number of accelerations and LTV were significantly higher in the last hour of labor, when compared to the initial hour. Discussion: The developed algorithm for on-line computer analysis of MHR recordings provided good to excellent computer-observer agreement and reliability. Moreover, it allowed an objective detection of MHR changes associated with labor progression, providing more information about the interpretation of maternal-fetal monitoring during labor. © 2014 Elsevier Ltd.
Keywords: Agreement; Cardiotocography; computer analysis; Fetal heart rate; Maternal heart rate; reliability

Dissecting the signaling pathways associated with the oncogenic activity of MLK3 P252H mutation - Velho, Sergia; Pinto, Ana; Licastro, Danilo; Oliveira, Maria Jose; Sousa, Filipa; Stupka, Elia; Seruca, Raquel (Bmc Cancer, 2014)

DNAJB4 molecular chaperone distinguishes WT from mutant E-cadherin, determining their fate in vitro and in vivo - Simões-Correia, J.; Silva, D.I.; Melo, S.; Figueiredo, J.; Caldeira, J.; Pinto, M.T.; Girão, H.; Pereira, P.; Seruca, R. (Human Molecular Genetics, 2014)
E-cadherin (Ecad) is a well-known invasion suppressor and its loss of expression is common in invasive carcinomas. Germline Ecad mutations are the only known genetic cause of hereditary diffuse gastric cancer (HDGC), demonstrating the causative role of Ecad impairment in gastric cancer. HDGC-associated Ecad missense mutations can lead to folding defects and premature proteasome-dependent endoplasmic reticulum-associated degradation (ERAD), but the molecular determinants for this fate were unidentified. Using a Drosophilabased genetic screen, we found that Drosophila DnaJ-1 interacts with wild type (WT) and mutant human Ecad in vivo. DnaJ (Hsp40) homolog, subfamily B, member 4 (DNAJB4), the human homolog of DnaJ-1, influences Ecad localization and stability even in the absence of Ecad endogenous promoter, suggesting a post-transcriptional level of regulation. Increased expression of DNAJB4 leads to stabilization of WT Ecad in the plasma membrane, while it induces premature degradation of unfolded HDGC mutants in the proteasome. The interaction between DNAJB4 and Ecad is direct, and is increased in the context of the unfolded mutant E757K, especially when proteasome degradation is inhibited, suggesting that DNAJB4 is a molecular mediator of ERAD. Post-translational regulation of native Ecad by DNAJB4 molecular chaperone is sufficient to influence cell adhesion in vitro. Using a chick embryo chorioallantoic membrane assay with gastric cancer derived cells, we demonstrate that DNAJB4 stimulates the anti-invasive function of WT Ecad in vivo. Additionally, the expression of DNAJB4 and Ecad is concomitantly decreased in human gastric carcinomas. Altogether, we demonstrate that DNAJB4 is a sensor of Ecad structural features that might contribute to gastric cancer progression. © The Author 2013. Published by Oxford University Press. All rights reserved.

Dysregulation of T cell receptor N-glycosylation: A molecular mechanism involved in ulcerative colitis - Dias, A.M.; Dourado, J.; Lago, P.; Cabral, J.; Marcos-Pinto, R.; Salgueiro, P.; Almeida, C.R.; Carvalho, S.; Fonseca, S.; Lima, M.; Vilanova, M.; Dinis-Ribeiro, M.; et al. (Human Molecular Genetics, 2014)
The incidence of inflammatory bowel disease is increasing worldwide and the underlying molecular mechanisms are far from being fully elucidated. Herein, we evaluated the role of N-glycosylation dysregulation in T cells as a key mechanism in the ulcerative colitis (UC) pathogenesis. The evaluation of the branched N-glycosylation levelsandprofile of intestinalTcell receptor (TCR)wereassessedin colonic biopsies fromUCpatientsand healthy controls. Expression alterations of the glycosyltransferase gene MGAT5 were also evaluated. We demonstrated thatUCpatients exhibit a dysregulation ofTCRbranchedN-glycosylationonlamina propriaTlymphocytes. Patients with severe UC showed the most pronounced defect on N-glycan branching in T cells. Moreover, UC patients showed a significant reduction of MGAT5 gene transcription in T lymphocytes. In this study, we disclose for the first time that a deficiency in branched N-glycosylation on TCR due to a reduced MGAT5 gene expression is a new molecular mechanism underlying UC pathogenesis, being a potential novel biomarker with promising clinical and therapeutic applications. © The Author 2013. Published by Oxford University Press. All rights reserved.

Endoplasmic Reticulum Degradation-Enhancing alpha-Mannosidase-like Protein 1 Targets Misfolded HLA-B27 Dimers for Endoplasmic Reticulum-Associated Degradation - Guiliano, David B.; Fussell, Helen; Lenart, Izabela; Tsao, Edward; Nesbeth, Darren; Fletcher, Adam J.; Campbell, Elaine C.; Yousaf, Nasim; Williams, Sarah; Santos, Susana; Cameron, Amy; Towers, Greg J.; et al. (Arthritis & Rheumatology, 2014)

Eradication of Helicobacter pylori: Past, present and future - Lopes, D.; Nunes, C.; Martins, M.C.L.; Sarmento, B.; Reis, S. (Journal of Controlled Release, 2014)
Helicobacter pylori is the major cause of chronic gastritis and peptic ulcers. Since the classification as a group 1 carcinogenic by International Agency for Research on Cancer, the importance of the complete H. pylori eradication has obtained a novel meaning. Hence, several studies have been made in order to deepen the knowledge in therapy strategies. However, the current therapy presents unsatisfactory eradication rates due to the lack of therapeutic compliance, antibiotic resistance, the degradation of antibiotics at gastric pH and their insufficient residence time in the stomach. Novel approaches have been made in order to overcome these limitations. The purpose of this review is to provide an overview about the current therapy and its limitations, while highlighting the possibility of using micro- and nanotechnology to develop gastric drug delivery systems, overcoming these difficulties in the future. © 2014 Elsevier B.V.
Keywords: Drug delivery; Helicobacter pylori; Microparticles; nanoparticles; Treatment

An evaluation of the latest in vitro tools for drug metabolism studies - Costa, A.; Sarmento, B.; Seabra, V. (Expert Opinion on Drug Metabolism and Toxicology, 2014)
Introduction: Drugs are indispensable for human welfare nevertheless there is a lack of safe drugs. Obtaining pharmacokinetics information, especially metabolism, is a requirement during preclinical and clinical drug development so that in vitro tools represent a simple path where it is possible to assess drug toxicity and predict drug safety in humans. Areas covered: This review covers the latest in vitro tools developed for assessing drug toxicity in different organs. A special focus is given to hepatic models, as it is the main organ responsible for drug metabolism and consequently bioactivation and detoxification reactions. Three-dimensional culture models have been widely developed, resembling in vivo-like conditions, and are also discussed in this review. Expert opinion: Several in vitro tools to assess hepatic drug metabolism have been developed, however, novel in vitro methods to investigate extra-hepatic drug metabolism still need to be improved. These methods are able to reduce the number of animal used in preclinical experiments, but in vivo tests are mandatory for drug approval and commercialization. © 2014 Informa UK, Ltd.
Keywords: Hepatic metabolism; in vitro models; Intestinal metabolism; Pulmonary metabolism; Renal metabolism

Extracellular matrix stiffness and composition jointly regulate the induction of malignant phenotypes in mammary epithelium - Chaudhuri, Ovijit; Koshy, Sandeep T.; Branco da Cunha, Cristiana; Shin, Jae-Won; Verbeke, Catia S.; Allison, Kimberly H.; Mooney, David J. (Nature Materials, 2014)

Field dimension and skill level constrain team tactical behaviours in small-sided and conditioned games in football - Silva, Pedro; Duarte, Ricardo; Sampaio, Jaime; Aguiar, Paulo; Davids, Keith; Araujo, Duarte; Garganta, Julio (Journal of Sports Sciences, 2014)
Si

Fluorescent bionanoprobes based on quantum dot-chitosan-O-phospho-L-serine conjugates for labeling human bone marrow stromal cells - Salgado, Christiane L.; Mansur, Alexandra A. P.; Mansur, Herman S.; Monteiro, Fernando J. M. (Rsc Advances, 2014)

Formulation and delivery of anti-HIV rectal microbicides: Advances and challenges - Nunes, Rute; Sarmento, Bruno; das Neves, Jose (Journal of Controlled Release, 2014)

Human umbilical cord tissue-derived mesenchymal stromal cells attenuate remodeling after myocardial infarction by proangiogenic, antiapoptotic, and endogenous cell-activation mechanisms - Nascimento, D.S.; Mosqueira, D.; Sousa, L.M.; Teixeira, M.; Filipe, M.; Resende, TP; Araújo, A.F.; Valente, M.; Almeida, J.; Martins, J.P.; Santos, J.M.; Bárcia, R.N.; et al. (Stem Cell Research and Therapy, 2014)
Introduction. Among the plethora of cells under investigation to restore a functional myocardium, mesenchymal stromal cells (MSCs) have been granted considerable interest. However, whereas the beneficial effects of bone marrow MSCs (BM-MSCs) in the context of the diseased heart are widely reported, data are still scarce on MSCs from the umbilical cord matrix (UCM-MSCs). Herein we report on the effect of UCM-MSC transplantation to the infarcted murine heart, seconded by the dissection of the molecular mechanisms at play. Methods. Human umbilical cord tissue-derived MSCs (UCX®), obtained by using a proprietary technology developed by ECBio, were delivered via intramyocardial injection to C57BL/6 females subjected to permanent ligation of the left descending coronary artery. Moreover, medium produced by cultured UCX® preconditioned under normoxia (CM) or hypoxia (CMH) was collected for subsequent in vitro assays. Results: Evaluation of the effects upon intramyocardial transplantation shows that UCX® preserved cardiac function and attenuated cardiac remodeling subsequent to myocardial infarction (MI). UCX® further led to increased capillary density and decreased apoptosis in the injured tissue. In vitro, UCX®-conditioned medium displayed (a) proangiogenic activity by promoting the formation of capillary-like structures by human umbilical vein endothelial cells (HUVECs), and (b) antiapoptotic activity in HL-1 cardiomyocytes subjected to hypoxia. Moreover, in adult murine cardiac Sca- 1§ssup§+§esup§ progenitor cells (CPCs), conditioned medium enhanced mitogenic activity while activating a gene program characteristic of cardiomyogenic differentiation. Conclusions: UCX® preserve cardiac function after intramyocardial transplantation in a MI murine model. The cardioprotective effects of UCX® were attributed to paracrine mechanisms that appear to enhance angiogenesis, limit the extent of the apoptosis, augment proliferation, and activate a pool of resident CPCs. Overall, these results suggest that UCX® should be considered an alternative cell source when designing new therapeutic approaches to treat MI. © 2014 Nascimento et al.; licensee BioMed Central Ltd.
Cited By (since 1996):2Export Date: 21 November 2014

Impact of 3-D printed PLA- and chitosan-based scaffolds on human monocyte/macrophage responses: Unraveling the effect of 3-D structures on inflammation - Almeida, C.R.; Serra, T.; Oliveira, M.I.; Planell, J.A.; Barbosa, M.A.; Navarro, M. (Acta Biomaterialia, 2014)
Recent studies have pointed towards a decisive role of inflammation in triggering tissue repair and regeneration, while at the same time it is accepted that an exacerbated inflammatory response may lead to rejection of an implant. Within this context, understanding and having the capacity to regulate the inflammatory response elicited by 3-D scaffolds aimed for tissue regeneration is crucial. This work reports on the analysis of the cytokine profile of human monocytes/macrophages in contact with biodegradable 3-D scaffolds with different surface properties, architecture and controlled pore geometry, fabricated by 3-D printing technology. Fabrication processes were optimized to create four different 3-D platforms based on polylactic acid (PLA), PLA/calcium phosphate glass or chitosan. Cytokine secretion and cell morphology of human peripheral blood monocytes allowed to differentiate on the different matrices were analyzed. While all scaffolds supported monocyte/macrophage adhesion and stimulated cytokine production, striking differences between PLA-based and chitosan scaffolds were found, with chitosan eliciting increased secretion of tumor necrosis factor (TNF)-α, while PLA-based scaffolds induced higher production of interleukin (IL)-6, IL-12/23 and IL-10. Even though the material itself induced the biggest differences, the scaffold geometry also impacted on TNF-α and IL-12/23 production, with chitosan scaffolds having larger pores and wider angles leading to a higher secretion of these pro-inflammatory cytokines. These findings strengthen the appropriateness of these 3-D platforms to study modulation of macrophage responses by specific parameters (chemistry, topography, scaffold architecture). © 2013 Acta Materialia Inc.
Cited By (since 1996):2Export Date: 21 November 2014
Keywords: 3-D scaffolds; Human macrophages; Inflammation; Rapid prototyping; Tissue engineering

The impact of nanoparticles on the mucosal translocation and transport of GLP-1 across the intestinal epithelium - Araújo, F.; Shrestha, N.; Shahbazi, M.-A.; Fonte, P.; Mäkilä, E.M.; Salonen, J.J.; Hirvonen, J.T.; Granja, P.L.; Santos, H.A.; Sarmento, B. (Biomaterials, 2014)
Glucagon like peptide-1 (GLP-1) is an incretin hormone that is in the pipeline for type 2 diabetes mellitus (T2DM) therapy. However, oral administration of GLP-1 is hindered by the harsh conditions of the gastrointestinal tract and poor bioavailability. In this study, three nanosystems composed by three different biomaterials (poly(lactide-co-glycolide) polymer (PLGA), Witepsol E85 lipid (solid lipid nanoparticles, SLN) and porous silicon (PSi) were developed and loaded with GLP-1 to study their permeability invitro. All the nanoparticles presented a size of approximately 200nm. The nanoparticles' interaction with the mucus and the intestinal cells were enhanced after coating with chitosan (CS). PSi nanosystems presented the best association efficiency (AE) and loading degree (LD), even though a high AE was also observed for PLGA nanoparticles and SLN. Among all the nanosystems, PLGA and PSi were the only nanoparticles able to sustain the release of GLP-1 in biological fluids when coated with CS. This characteristic was also maintained when the nanosystems were in contact with the intestinal Caco-2 and HT29-MTX cell monolayers. The CS-coated PSi nanoparticles showed the highest GLP-1 permeation across the intestinal invitro models. In conclusion, PLGA+CS and PSi+CS are promising nanocarriers for the oral delivery of GLP-1. © 2014 Elsevier Ltd.
Keywords: chitosan; Diabetes; Glucagon like peptide-1; nanoparticles; Oral delivery systems; Triple co-culture

In vitro intestinal absorption of amino acid mixtures extracted from codfish (Gadus morhua L.) salting wastewater - Ferraro, V.; Ferreira Jorge, R.; Cruz, I.B.; Antunes, F.; Sarmento, B.; Castro, P.M.L.; Pintado, M.E. (International Journal of Food Science and Technology, 2014)
Summary: This study reports on the intestinal permeability of salt-containing mixtures of amino acids extracted from codfish salting wastewater. Permeability was evaluated in vitro using the Caco-2 cell line model; cell integrity during exposure to mixtures of amino acids was estimated by measuring the transepithelial electrical resistance (TEER). The effect of salt (NaCl) on the permeability and on the intestinal cell's integrity was also examined. Permeation rate (i.e. transport) was ≥95% for all amino acids except for creatine, for which it was 6%. Values for apparent permeability coefficients, Papp > 10-5 cm s-1, for mixture with isotonic concentration of NaCl suggest that amino acids are very likely to be absorbed in humans. Mixture with a hypertonic level of NaCl exerts a cytotoxic effect in intestinal cells resulting in a loss of epithelium integrity. Results show that isotonic mixture of amino acids extracted from codfish salting wastewater could be used in food, feed, cosmetic and pharmaceutical formulations. These applications could contribute to the fish industry sustainability. © 2013 Institute of Food Science and Technology.
Keywords: Absorption; Amino acids; Caco-2 cell; Codfish; Small intestine

Injectable MMP-sensitive alginate hydrogels as hMSC delivery systems - Fonseca, K.B.; Gomes, D.B.; Lee, K.; Santos, S.G.; Sousa, A.; Silva, E.A.; Mooney, D.J.; Granja, P.L.; Barrias, C.C. (Biomacromolecules, 2014)
Hydrogels with the potential to provide minimally invasive cell delivery represent a powerful tool for tissue-regeneration therapies. In this context, entrapped cells should be able to escape the matrix becoming more available to actively participate in the healing process. Here, we analyzed the performance of proteolytically degradable alginate hydrogels as vehicles for human mesenchymal stem cells (hMSC) transplantation. Alginate was modified with the matrix metalloproteinase (MMP)-sensitive peptide Pro-Val-Gly-Leu-Iso-Gly (PVGLIG), which did not promote dendritic cell maturation in vitro, neither free nor conjugated to alginate chains, indicating low immunogenicity. hMSC were entrapped within MMP-sensitive and MMP-insensitive alginate hydrogels, both containing cell-adhesion RGD peptides. Softer (2 wt % alginate) and stiffer (4 wt % alginate) matrices were tested. When embedded in a Matrigel layer, hMSC-laden MMP-sensitive alginate hydrogels promoted more extensive outward cell migration and invasion into the tissue mimic. In vivo, after 4 weeks of subcutaneous implantation in a xenograft mouse model, hMSC-laden MMP-sensitive alginate hydrogels showed higher degradation and host tissue invasion than their MMP-insensitive equivalents. In both cases, softer matrices degraded faster than stiffer ones. The transplanted hMSC were able to produce their own collagenous extracellular matrix, and were located not only inside the hydrogels, but also outside, integrated in the host tissue. In summary, injectable MMP-sensitive alginate hydrogels can act as localized depots of cells and confer protection to transplanted cells while facilitating tissue regeneration. © 2013 American Chemical Society.
Cited By (since 1996):3Export Date: 21 November 2014

Long-term effects of chronic cocaine exposure throughout adolescence on anxiety and stress responsivity in a Wistar rat model - Alves, C.J.; Magalhães, A.; Melo, P.; De Sousa, L.; Tavares, M.A.; Monteiro, P.R.R.; Summavielle, T. (Neuroscience, 2014)
Adolescents display increased vulnerability to engage in drug experimentation. This is often considered a risk factor for later drug abuse. In this scenario, the permanent effects of cocaine exposure during adolescence on anxiety levels and stress responsivity, which may result in behavioral phenotypes prone to addiction, are now starting to be unveiled. Thus, the purpose of the present study was to evaluate the long-lasting effects of chronic cocaine administration during adolescence, on anxiety-like behavior and on stress response. Adolescent male Wistar rats were daily administered 45-mg cocaine/kg of body weight in three equal intraperitoneal doses with 1-h interval, from postnatal day (PND) 35 to 50. The effects of cocaine administration on anxiety levels, assessed in the Elevated Plus Maze (EPM), and on social stress response, assessed in the resident-intruder paradigm (R/I), were evaluated 10. days after withdrawal, when rats were reaching the adulthood. The underlying dopaminergic activity, and the corticosterone and testosterone levels were determined. Our results showed that cocaine induced long-lasting alterations in the hypothalamus-pituitary-adrenals (HPA) axis function and in testosterone levels. Such alterations resulted in significant and enduring changes in behavioral responses to environmental challenges, such as the EPM and R/I, including the evaluation of potential threats that may lead to high-risk behavior and low-benefit choices. This was further supported by an altered dopaminergic function in the amygdala and hippocampus. The present findings provide new insights into how the use of cocaine during adolescent development may modulate emotional behavior later in life. Compromised ability to recognize and deal with potential threats is an important risk factor to perpetuate compulsive drug seeking and relapse susceptibility. © 2014 IBRO.
Keywords: Adolescence; anxiety; Cocaine; corticosterone; Dopaminergic system; Social stress

Macrophages stimulate gastric and colorectal cancer invasion through EGFR Y 1086, c-Src, Erk1/2 and Akt phosphorylation and smallGTPase activity - Cardoso, A.P.; Pinto, M.L.; Pinto, A.T.; Oliveira, M.I.; Pinto, M.T.; Gonçalves, R.; Relvas, J.B.; Figueiredo, C.; Seruca, R.; Mantovani, A.; Mareel, M.; Barbosa, M.A.; et al. (Oncogene, 2014)
The interactions between cancer cells and their microenvironment are crucial for malignant progression, as they modulate invasion-related activities. Tumor-associated macrophages are generally considered allies in the process of tumor progression in several types of cancer, although their role on gastric and colorectal carcinomas is still poorly understood. In this report, we studied the influence of primary human macrophages on gastric and colorectal cancer cells, considering invasion, motility/migration, proteolysis and activated intracellular signaling pathways. We demonstrated that macrophages stimulate cancer cell invasion, motility and migration, and that these effects depend on matrix metalloproteinase (MMP) activity and on the activation of epidermal growth factor receptor (EGFR) (at the residue Y 1086), PLC-γ (phospholipase C-gamma) and Gab1 (GRB2-associated binding protein-1), as evidenced by siRNA (small interference RNA) experiments. Epidermal growth factor (EGF)-immunodepletion impaired macrophage-mediated cancer cell invasion and motility, suggesting that EGF is the pro-invasive and pro-motile factor produced by macrophages. Macrophages also induced gastric and colorectal cancer cell phosphorylation of Akt, c-Src and ERK1/2, and led to an increase of RhoA and Cdc42 activity. Interestingly, whereas macrophage-mediated cancer cell c-Src and ERK1/2 phosphorylation occurred downstream EGFR activation, Akt phosphorylation seems to be a parallel event, taking place in an EGFR-independent manner. The involvement of EGF, EGFR-downstream signaling partners and MMPs in macrophage-mediated invasion provides novel insights into the molecular crosstalk established between cancer cells and macrophages, opening new perspectives for the design of new and more efficient therapeutic strategies to counteract cancer cell invasion. © 2014 Macmillan Publishers Limited.
Cited By (since 1996):2Export Date: 21 November 2014
Keywords: cancer cell invasion; colon cancer; Gastric cancer; invasion-related signaling pathways; Macrophages; tumor microenvironment

Mad2 checkpoint gene silencing using epidermal growth factor receptor-targeted chitosan nanoparticles in non-small cell lung cancer model - Nascimento, A.V.; Singh, A.; Bousbaa, H.; Ferreira, D.; Sarmento, B.; Amiji, M.M. (Molecular Pharmaceutics, 2014)
RNA interference has emerged as a powerful strategy in cancer therapy because it allows silencing of specific genes associated with tumor progression and resistance. Mad2 is an essential mitotic checkpoint component required for accurate chromosome segregation during mitosis, and its complete abolition leads to cell death. We have developed an epidermal growth factor receptor (EGFR)-targeted chitosan system for silencing the Mad2 gene as a strategy to efficiently induce cell death in EGFR overexpressing human A549 non-small cell lung cancer cells. Control and EGFR-targeted chitosan nanoparticles loaded with small interfering RNAs (siRNAs) against Mad2 were formulated and characterized for size, charge, morphology, and encapsulation efficiency. Qualitative and quantitative intracellular uptake studies by confocal imaging and flow cytometry, respectively, showed time-dependent enhanced and selective intracellular internalization of EGFR-targeted nanoparticles compared to nontargeted system. Targeted nanoparticles showed nearly complete depletion of Mad2 expression in A549 cells contrasting with the partial depletion in the nontargeted system. Accordingly, Mad2-silencing-induced apoptotic cell death was confirmed by cytotoxicity assay and flow cytometry. Our results demonstrate that EGFR-targeted chitosan loaded with Mad2 siRNAs is a potent delivery system for selective killing of cancer cells.
Keywords: chitosan nanoparticles; Epidermal growth factor receptor; Mad2 gene; non-small cell lung cancer; RNA interference; tumor targeting

Magnetic Bioinspired Hybrid Nanostructured Collagen-Hydroxyapatite Scaffolds Supporting Cell Proliferation and Tuning Regenerative Process - Tampieri, Anna; Iafisco, Michele; Sandri, Monica; Panseri, Silvia; Cunha, Carla; Sprio, Simone; Savini, Elisa; Uhlarz, Marc; Herrmannsdoerfer, Thomas (Acs Applied Materials & Interfaces, 2014)

Modified-chitosan/siRNA nanoparticles downregulate cellular CDX2 expression and cross the gastric mucus barrier - Sadio, A.; Gustafsson, J.K.; Pereira, B.; Gomes, C.P.; Hansson, G.C.; David, L.; Pêgo, A.P.; Almeida, R. (PLoS ONE, 2014)
Development of effective non-viral vectors is of crucial importance in the implementation of RNA interference in clinical routine. The localized delivery of siRNAs to the gastrointestinal mucosa is highly desired but faces specific problems such as the stability in gastric acidity conditions and the presence of the mucus barrier. CDX2 is a transcription factor critical for intestinal differentiation being involved in the initiation and maintenance of gastrointestinal diseases. Specifically, it is the trigger of gastric intestinal metaplasia which is a precursor lesion of gastric cancer. Its expression is also altered in colorectal cancer, where it may constitute a lineage-survival oncogene. Our main objective was to develop a nanoparticle-delivery system of siRNA targeting CDX2 using modified chitosan as a vector. CDX2 expression was assessed in gastric carcinoma cell lines and nanoparticles behaviour in gastrointestinal mucus was tested in mouse explants. We show that imidazolemodified chitosan and trimethylchitosan/siRNA nanoparticles are able to downregulate CDX2 expression and overpass the gastric mucus layer but not colonic mucus. This system might constitute a potential therapeutic approach to treat CDX2-dependent gastric lesions. © 2014 Sadio et al.

Modulation of human dermal microvascular endothelial cell and human gingival fibroblast behavior by micropatterned silica coating surfaces for zirconia dental implant applications - Laranjeira, M.S.; Carvalho, Â.; Pelaez-Vargas, A.; Hansford, D.; Ferraz, M.P.; Coimbra, S.; Costa, E.; Santos-Silva, A.; Fernandes, M.H.; Monteiro, F.J. (Science and Technology of Advanced Materials, 2014)
Dental ceramic implants have shown superior esthetic behavior and the absence of induced allergic disorders when compared to titanium implants. Zirconia may become a potential candidate to be used as an alternative to titanium dental implants if surface modifications are introduced. In this work, bioactive micropatterned silica coatings were produced on zirconia substrates, using a combined methodology of sol-gel processing and soft lithography. The aim of the work was to compare the in vitro behavior of human gingival fibroblasts (HGFs) and human dermal microvascular endothelial cells (HDMECs) on three types of silica-coated zirconia surfaces: flat and micropatterned (with pillars and with parallel grooves). Our results showed that cells had a higher metabolic activity (HGF, HDMEC) and increased gene expression levels of fibroblast-specific protein-1 (FSP-1) and collagen type I (COL I) on surfaces with pillars. Nevertheless, parallel grooved surfaces were able to guide cell growth. Even capillary tube-like networks of HDMEC were oriented according to the surface geometry. Zirconia and silica with different topographies have shown to be blood compatible and silica coating reduced bacteria adhesion. All together, the results indicated that microstructured bioactive coating seems to be an efficient strategy to improve soft tissue integration on zirconia implants, protecting implants from peri-implant inflammation and improving long-term implant stabilization. This new approach of micropatterned silica coating on zirconia substrates can generate promising novel dental implants, with surfaces that provide physical cues to guide cells and enhance their behavior. © 2014 National Institute for Materials Science.
Keywords: bacteria adhesion; Biomaterials; hemolysis; human dermal microvascular endothelial cells (HDMECs); human gingival fibroblasts (HGFs); Micropatterning; Soft lithography

Mucoadhesive polymers in the design of nano-drug delivery systems for administration by non-parenteral routes: A review - Sosnik, Alejandro; das Neves, Jose; Sarmento, Bruno (Progress in Polymer Science, 2014)

Nanoparticle-based drug delivery to improve the efficacy of antiretroviral therapy in the central nervous system - Gomes, M.J.; Das Neves, J.; Sarmento, B. (International Journal of Nanomedicine, 2014)
Antiretroviral drug therapy plays a cornerstone role in the treatment of human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome patients. Despite obvious advances over the past 3 decades, new approaches toward improved management of infected individuals are still required. Drug distribution to the central nervous system (CNS) is required in order to limit and control viral infection, but the presence of natural barrier structures, in particular the blood-brain barrier, strongly limits the perfusion of anti-HIV compounds into this anatomical site. Nanotechnology-based approaches may help providing solutions for antiretro-viral drug delivery to the CNS by potentially prolonging systemic drug circulation, increasing the crossing and reducing the efflux of active compounds at the blood-brain barrier, and providing cell/tissue-targeting and intracellular drug delivery. After an initial overview on the basic features of HIV infection of the CNS and barriers to active compound delivery to this anatomical site, this review focuses on recent strategies based on antiretroviral drug-loaded solid nanoparticles and drug nanosuspensions for the potential management of HIV infection of the CNS. © 2014 Gomes et al.
Keywords: Blood-brain barrier; drug targeting; Efflux transporters; HIV/AIDS; Protease inhibitors

Natriuretic peptide system modulation in uninephrectomized rats - Santos-Araújo, C.; Roncon-Albuquerque Jr., R.; Moreira-Rodrigues, M.; Henriques-Coelho, T.; Quelhas-Santos, J.; Faria, B.; Sampaio-Maia, B.; Leite-Moreira, A.F.; Pestana, M. (Experimental and Clinical Cardiology, 2014)
BACKGROUND: Cardiac activation of the natriuretic peptide (NP) system plays a major role in the renal adaptations to volume, expansion (VE). However, its role after uninephrectomy (Unx) remains to be elucidated. In the present study, we evaluated cardiac hemodynamics, plasma NP-Type B (BNP) levels nd NP receptor A (NPR-A) and C (NPR-C) expression in the renal cortex (RC) and medulla (RM) of Sham and Unx rats. METHODS: Male Wistar-Han rats (n=42) were randomly assigned to Unx or Sham surgery. Non-invasive blood pressure (BP), invasive left ventricular (LV) hemodynamics and natriuretic response to VE were performed and plasma was collected for BNP determination, 2, 10 and 26 weeks after surgery. In addition, samples from RC and RM were obtained for NPR-A and -C quantification (RT-PCR and western-blot). RESULTS: In Unx, blood pressure elevation and reduced natriuretic response to VE were observed. Although plasma BNP levels increased overtime, no LV dysfunction or myocardial BNP gene activation was observed in Unx. NPR-A mRNA in RC and RM were significantly increased in Unx at 26 weeks. This was accompanied by decreased NPR-C mRNA in the RM in Unx at 10 and 26 weeks, with no differences detected in the RC. CONCLUSIONS: In our experimentalmodel of Unx, progressive BP elevation and reduced natriuretic response to VE were accompanied by modulation of NPR-A and -C expression, in both the RC and RM, in the absence of cardiac activation of the NP system. Our results suggest a local renal modulation of the NP system after Unx. © 2013 et al.; licensee Cardiology Academic Press.
Keywords: BNP; Hypertension; Natriuretic peptide receptor; Uninephrectomy

Neonatal human dermal fibroblasts immobilized in RGD-alginate induce angiogenesis - Guerreiro, S.G.; Oliveira, M.J.; Barbosa, M.A.; Soares, R.; Granja, P.L. (Cell Transplantation, 2014)
Promoting angiogenesis in a damaged tissue is a major challenge for tissue regeneration. Recent findings in tissue engineering suggest that fibroblasts (FBs) play an important role in orchestrating the angiogenic process. Fibroblasts maintain the structural integrity of connective tissue by continuously secreting growth factors and extracellular matrix precursors, which are essential for endothelial cell (EC) adhesion and spreading, thus playing a crucial role in angiogenesis. We hypothesized that FBs immobilized in alginate gels grafted with the RGD peptidic sequence could influence the recruitment of ECs to improve vascularization. In this work, the modulation of immobilized human FBs within the 3D synthetic extracellular matrix was assessed. Experiments using cocultures of ECs and FBs in indirect contact as well as angiogenic assays were performed to assess the influence of FBs immobilized in RGD-alginate in ECs' viability, stabilization, sprouting, and assembly into capillary-like structures. This study demonstrates the ability of FBs immobilized within RGD-alginate microspheres to modulate and support capillary-like structures' assembly. These findings indicate that the microenvironment created by these stromal cells in the scaffold modulates capillary morphogenesis, thus stimulating angiogenesis in situ and can potentially be used in regenerative medicine in clinical scenarios where vascularization is essential. © 2014 Cognizant Comm. Corp.
Keywords: Alginate; angiogenesis; Endothelial cells (ECs); Fibroblasts (FBs); RGD peptide: Injectable biomaterials

Optimization of the production of solid Witepsol nanoparticles loaded with rosmarinic acid - Campos, D.A.; Madureira, A.R.; Gomes, A.M.; Sarmento, B.; Pintado, M.M. (Colloids and Surfaces B: Biointerfaces, 2014)
During the last decade there has been a growing interest in the formulation of new food and nutraceutical products containing compounds with antioxidant activity. Unfortunately, due to their structure, certain compounds such as polyphenols, in particular rosmarinic acid (RA) are not stable and may interact easily with matrices in which they are incorporated. To overcome such limitations, the formulation of loaded polyphenols nanoparticles can offer an efficient solution to protect such compounds. Based on this rationale, the aim of this study was to prepare solid lipid nanoparticles (SLNs) loaded with RA using a hot melt ultrasonication method, where Witepsol H15 was used as lipid and Polysorbate 80 (Tween 80) as surfactant, following a 32 fractional factorial design, resulting in the use of 3 different percentages of surfactant (viz. 1, 2 and 3%, v/v) and lipid (0.5, 1.0 and 1.5%, w/v). The stability of the nanoparticles systems were tested during 28d in aqueous solution stored at refrigeration temperature (ca. 5°C), tracking the mean particle size of different formulations by photon correlation spectroscopy. To confirm RA entrapment, thermal analyses of the nanoparticles by DSC and FTIR were performed. The association efficiencies percentages (AE%) were determined using HPLC to quantitatively assess the RA in supernatants. Results showed that Witepsol H15 produced nanoparticles with initial mean diameters between 270 and 1000nm, yet over time, a slight increase occurred, but without occurrence of aggregation. The AE% showed a high percentage of encapsulation (ca. 99%), which reveals low polyphenol releases from SLNs throughout storage time. In general, results showed a successful production of SLNs with properties that can be used to food applications. © 2013 Elsevier B.V.
Keywords: Optimization; Rosmarinic acid; SLNs; Witepsol

Plasma and urine renalase levels and activity during the recovery of renal function in kidney transplant recipients - Quelhas-Santos, J.; Soares-Silva, I.; Fernandes-Cerqueira, C.; Simões-Silva, L.; Ferreira, I.; Carvalho, C.; Coentrão, L.; Vaz, R.; Sampaio-Maia, B.; Pestana, M. (Experimental Biology and Medicine, 2014)
Renalase is a recently described enzyme secreted by the kidney into both plasma and urine, where it was suggested to degrade catecholamines contributing to blood pressure control. While there is a controversy regarding the relationship between renal function and plasma renalase levels, there is virtually no data in humans on plasma renalase activity as well as on both urine renalase levels and activity. We prospectively examined the time course of plasma and urine renalase levels and activity in 26 end-stage renal disease (ESRD) patients receiving a cadaver kidney transplant (cadaver kidney recipients [CKR]) before surgery and during the recovery of renal function up to day 90 post transplant. The relationship with sympathetic and renal dopaminergic activities was also evaluated. The recovery of renal function in CKR closely predicted decreases in plasma renalase levels (r = 0.88; P < 0.0001), urine renalase levels (r = 0.75; P < 0.0001) and urine renalase activity (r = 0.56; P < 0.03), but did not predict changes in plasma renalase activity (r = -0.02; NS). Plasma norepinephrine levels positively correlated with plasma renalase levels (r = 0.64, P < 0.002) as well as with urine renalase levels and activity (r = 0.47 P < 0.02; r = 0.71, P < 0.0005, respectively) and negatively correlated with plasma renalase activity (r = -0.57, P < 0.002). By contrast, plasma epinephrine levels positively correlated with plasma renalase activity (r = 0.67, P < 0.0001) and negatively correlated with plasma renalase levels (r = -0.62, P < 0.003). A significant negative relationship was observed between urine dopamine output and urine renalase levels (r = -0.48; P < 0.03) but not with urine renalase activity (r = -0.33, NS). We conclude that plasma and urine renalase levels closely depend on renal function and sympathetic nervous system activity. It is suggested that epinephrine-mediated activation of circulating renalase may occur in renal transplant recipients with good recovery of renal function. The increase in plasma renalase activity observed in ESRD patients and renal transplant recipients can be explained on the basis of reduced inhibition of the circulating enzyme. © 2014 by the Society for Experimental Biology and Medicine.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: catecholamines; CKD; renal function; renal transplant; renalase

The potential utility of chitosan micro/nanoparticles in the treatment of gastric infection - Gonçalves, I.C.; Henriques, P.C.; Seabra, C.L.; Martins, M.C.L. (Expert Review of Anti-Infective Therapy, 2014)
Gastric infections are mainly caused by Helicobacter pylori (H. pylori), a bacterium that colonizes the gastric mucosa of over 50% of the world's population. Chronic H. pylori infection has been associated with gastric diseases such as chronic gastritis, peptic ulcer and gastric adenocarcinoma. Current eradication treatment relies on antibiotic-based therapies that are unsuccessful in approximately 20% of the patients. Chitosan, a natural and cationic polysaccharide has been investigated in the treatment of H. pylori infection. Due to its mucoadhesive properties, it has been used in the form of micro/nanoparticles, polyelectrolyte complexes or coatings as antibiotic encapsulation systems for gastric delivery, but alternative molecules may also be incorporated. It has been recently proposed that chitosan can also be used for H. pylori binding and scavenging from the host stomach due to its antimicrobial/binding properties. In this manuscript, a brief description of the use of chitosan in H. pylori treatment is reviewed. © Informa UK, Ltd.
Keywords: Biomaterials; chitosan; Crosslinking; Drug delivery; Gastric cancer; Helicobacter pylori; Microspheres; mucoadhesion; nanoparticles; Polyelectrolytes

The predominance of M2-polarized macrophages in the stroma of low-hypoxic bladder tumors is associated with BCG immunotherapy failure - Lima, L.; Oliveira, D.; Tavares, A.; Amaro, T.; Cruz, R.; Oliveira, M.J.; Ferreira, J.A.; Santos, L. (Urologic Oncology: Seminars and Original Investigations, 2014)
Objective: Bacillus Calmette-Guérin (BCG) immunotherapy is the gold standard treatment for superficial bladder tumors with intermediate/high risk of recurrence or progression. However, approximately 30% of patients fail to respond to the treatment. Effective BCG therapy needs precise activation of the type 1 helper cells immune pathway. Tumor-associated macrophages (TAMs) often assume an immunoregulatory M2 phenotype and may directly interfere with the BCG-induced antitumor immune response. Thus, we aim to clarify the influence of TAMs, in particular of the M2 phenotype in stroma and tumor areas, in BCG treatment outcome. Patients and methods: The study included 99 patients with bladder cancer treated with BCG. Tumors resected before treatment were evaluated using immunohistochemistry for CD68 and CD163 antigens, which identify a lineage macrophage marker and a M2-polarized specific cell surface receptor, respectively. CD68+ and CD163+ macrophages were evaluated within the stroma and tumor areas, and high density of infiltrating cells spots were selected for counting. Hypoxia, an event known to modulate macrophage phenotype, was also assessed through hypoxia induced factor (HIF)-1α expression. Results: Patients in whom BCG failed had high stroma-predominant CD163+ macrophage counts (high stroma but low tumor CD163+ macrophages counts) when compared with the ones with a successful treatment (71% vs. 47%, P = 0.017). Furthermore, patients presenting this phenotype showed decreased recurrence-free survival (log rank, P = 0.008) and a clear 2-fold increased risk of BCG treatment failure was observed in univariate analysis (hazard ratio = 2.343; 95% CI: 1.197-4.587; P = 0.013). Even when adjusted for potential confounders, such as age and therapeutic scheme, multivariate analysis revealed 2.6-fold increased risk of recurrence (hazard ratio = 2.627; 95% CI: 1.340-5.150; P = 0.005). High stroma-predominant CD163+ macrophage counts were also associated with low expression of HIF-1α in tumor areas, whereas high counts of CD163+ in the tumor presented high expression of HIF-1α in tumor nests. Conclusions: TAMs evaluation using CD163 is a good indicator of BCG treatment failure. Moreover, elevated infiltration of CD163+ macrophages, predominantly in stroma areas but not in the tumor, may be a useful indicator of BCG treatment outcome, possibly owing to its immunosuppressive phenotype. © 2014 Elsevier Inc.
Keywords: BCG immunotherapy; Bladder cancer; CD163; CD68; Tumor-associated macrophages

Primary bone marrow mesenchymal stromal cells rescue the axonal phenotype of twitcher mice - Miranda, C.O.; Teixeira, C.A.; Sousa, V.F.; Santos,TE; Liz, M.A.; Marques,AM; Pinto-Do-Ó, P.; Sousa, M.M. (Cell Transplantation, 2014)
Krabbe's disease (KD) is a demyelinating disorder caused by the deficiency of lysosomal galactocerebrosidase (GALC), affecting both the central (CNS) and the peripheral nervous system (PNS). A current therapy, hematopoietic stem cell transplantation (HSCT), is ineffective at correcting the PNS pathology. We have previously shown that systemic delivery of immortalized bone marrow-derived murine mesenchymal stromal cells (BM-MSCs) diminishes the neuropathology of transplanted Twitcher mice, a murine model of KD. In this study, to move one step closer to clinical application, the effectiveness of a systematic delivery of primary BM-MSCs to promote recovery of the Twitcher PNS was assessed. Primary BM-MSCs grafted to the Twitcher sciatic nerve led to increased GALC activity that was not correlated to decreased psychosine (the toxic GALC substrate) accumulation. Nevertheless, BM-MSC transplantation rescued the axonal phenotype of Twitcher mice in the sciatic nerve, with an increased density of both myelinated and unmyelinated axons in transplanted animals. Whereas no increase in myelination was observed, upon transplantation an increased proliferation of Schwann cell precursors occurred. Supporting these findings, in vitro, BM-MSCs promoted neurite outgrowth of Twitcher sensory neurons and proliferation of Twitcher Schwann cells. Moreover, BM-MSCs expressed nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) and promoted increased BDNF synthesis by neighboring Schwann cells. Besides their action in neurons and glia, BM-MSCs led to macrophage activation in Twitcher sciatic nerves. In summary, primary BM-MSCs diminish the neuropathology of Twitcher sciatic nerves by coordinately affecting neurons, glia, and macrophages. © 2014 Cognizant Comm. Corp.
Cited By (since 1996):2Export Date: 21 November 2014
Keywords: Axonal degeneration; Bone marrow-derived mesenchymal stromal cells (BM-MSCs); Krabbe's disease (KD); Twitcher mice

Production, characterization and biocompatibility of marine collagen matrices from an alternative and sustainable source: The sea urchin Paracentrotus lividus - Di Benedetto, C.; Barbaglio, A.; Martinello, T.; Alongi, V.; Fassini, D.; Cullorà, E.; Patruno, M.; Bonasoro, F.; Barbosa, M.A.; Carnevali, M.D.C.; Sugni, M. (Marine Drugs, 2014)
Collagen has become a key-molecule in cell culture studies and in the tissue engineering field. Industrially, the principal sources of collagen are calf skin and bones which, however, could be associated to risks of serious disease transmission. In fact, collagen derived from alternative and riskless sources is required, and marine organisms are among the safest and recently exploited ones. Sea urchins possess a circular area of soft tissue surrounding the mouth, the peristomial membrane (PM), mainly composed by mammalian-like collagen. The PM of the edible sea urchin Paracentrotus lividus therefore represents a potential unexploited collagen source, easily obtainable as a food industry waste product. Our results demonstrate that it is possible to extract native collagen fibrils from the PM and produce suitable substrates for in vitro system. The obtained matrices appear as a homogeneous fibrillar network (mean fibril diameter 30-400 nm and < 2 μm) and display remarkable mechanical properties in term of stiffness (146 ± 48 MPa) and viscosity (60.98 ± 52.07 GPa·s). In vitro tests with horse pbMSC show a good biocompatibility in terms of overall cell growth. The obtained results indicate that the sea urchin P. lividus can be a valuable low-cost collagen source for mechanically resistant biomedical devices.
Keywords: Biocompatibility; Collagen matrix; Mesenchimal stromal cells; Native fibril; Sea urchin collagen; Tissue regeneration

Propolis varnish: Antimicrobial properties against cariogenic bacteria, cytotoxicity, and sustained-release profile - De Luca, M.P.; Franca, J.R.; Macedo, F.A.F.F.; Grenho, L.; Cortes, M.E.; Faraco, A.A.G.; Moreira, A.N.; Santos, V.R. (BioMed Research International, 2014)
Varnishes are preparations that differ in the polymeric matrix and therapeutical agents. In dentistry they are used to prevent caries. In this study we developed a propolis varnish, considering propolis properties against cariogenic bacteria. To a chitosan polymeric base (CHV) was added ethanolic propolis extract in different concentrations: PV1 (5%), PV2 (10%), and PV3 (15%). Antimicrobial activity was carried out against Streptococcus mutans (SM), Streptococcus sanguinis (SG), Streptococcus salivarius (SS), and Lactobacillus casei (LC) through agar diffusion method. The three propolis concentrations incorporated were effective in inhibiting the growth of all microorganisms, but without significant difference between the zones of inhibition observed. Cytotoxicity assay was done by MTT method. Data were analyzed by one-way ANOVA and Bonferroni test. None of the varnishes were cytotoxic, keeping 80% of viable cells, while CHV allowed cellular proliferation (120%). Sustained-release test was carried out by applying 40 μL of each varnish in the buccal surface of bovine teeth and kept in an ethanol/water solution removed in regular times. According to the "independent model approach," the release profiles were distinct from each varnish and the most prolonged was PV3 (8 weeks). Varnish formulations had satisfactory antimicrobial activity against cariogenic bacteria and have a low cytotoxicity (<50%). © 2014 Mariana P. De Luca et al.

Quality by Design: Discussing and Assessing the Solid Dispersions Risk - Chaves, Luise L.; Vieira, Alexandre C. C.; Reis, Salette; Sarmento, Bruno; Ferreira, Domingos C. (Current Drug Delivery, 2014)

Rescue of wild-type E-cadherin expression from nonsense-mutated cancer cells by a suppressor-tRNA - Bordeira-Carriço, R.; Ferreira, D.; Mateus, D.D.; Pinheiro, H.; Pêgo, A.P.; Santos, M.A.S.; Oliveira, C. (European Journal of Human Genetics, 2014)
Hereditary diffuse gastric cancer (HDGC) syndrome, although rare, is highly penetrant at an early age, and is severe and incurable because of ineffective screening tools and therapy. Approximately 45% of HDGC families carry germline CDH1/E-cadherin alterations, 20% of which are nonsense leading to premature protein truncation. Prophylactic gastrectomy is the only recommended approach for all asymptomatic CDH1 mutation carriers. Suppressor-tRNAs can replace premature stop codons (PTCs) with a cognate amino acid, inducing readthrough and generating full-length proteins. The use of suppressor-tRNAs in HDGC patients could therefore constitute a less invasive therapeutic option for nonsense mutation carriers, delaying the development of gastric cancer. Our analysis revealed that 23/108 (21.3%) of E-cadherin-mutant families carried nonsense mutations that could be potentially corrected by eight suppressor-tRNAs, and arginine was the most frequently affected amino acid. Using site-directed mutagenesis, we developed an arginine suppressor-tRNA vector to correct one HDGC nonsense mutation. E-cadherin-deficient cell lines were transfected with plasmids carrying simultaneously the suppressor-tRNA and wild-type or mutant CDH1 mini-genes. RT-PCR, western blot, immunofluorescence, flow cytometry and proximity ligation assay (PLA) were used to establish the model, and monitor mRNA and protein expression and function recovery from CDH1 vectors. Cells expressing a CDH1 mini-gene, carrying a nonsense mutation and the suppressor-tRNA, recovered full-length E-cadherin expression and its correct localization and incorporation into the adhesion complex. This is the first demonstration of functional recovery of a mutated causative gene in hereditary cancer by cognate amino acid replacement with suppressor-tRNAs. Of the HDGC families, 21.3% are candidates for correction with suppressor-tRNAs to potentially delay cancer onset. © 2014 Macmillan Publishers Limited. All rights reserved.
Keywords: hereditary diffuse gastric cancer (HDGC); nonsense suppression; Premature termination codon (PTC); Suppressor-tRNA

Resveratrol as a Natural Anti-Tumor Necrosis Factor-alpha Molecule: Implications to Dendritic Cells and Their Crosstalk with Mesenchymal Stromal Cells - Silva, Andreia M.; Oliveira, Marta I.; Sette, Laura; Almeida, Catarina R.; Oliveira, Maria J.; Barbosa, Mario A.; Santos, Susana G. (Plos One, 2014)

Role of sparc in bone remodeling and cancer-related bone metastasis - Ribeiro, N.; Sousa, S.R.; Brekken, R.A.; Monteiro, F.J. (Journal of Cellular Biochemistry, 2014)
There is a growing socioeconomic recognition that clinical bone diseases such as bone infections, bone tumors and osteoporotic bone loss mainly associated with ageing, are major issues in today's society. SPARC (secreted protein, acidic and rich in cysteine), a matricellular glycoprotein, may be a promising therapeutic target for preventing or treating bone-related diseases. In fact, SPARC is associated with tissue remodeling, repair, development, cell turnover, bone mineralization and may also participate in growth and progression of tumors, namely cancer-related bone metastasis. Yet, the function of SPARC in such biological processes is poorly understood and controversial. The main objective of this work is to review the current knowledge related to the activity of SPARC in bone remodeling, tumorigenesis, and bone metastasis. Progress in understanding SPARC biology may provide novel strategies for bone regeneration and the development of anti-angiogenic, anti-proliferative, or counter-adhesive treatments specifically against bone metastasis. © 2013 Wiley Periodicals, Inc. © 2013 Wiley Periodicals, Inc.
Keywords: BONE METASTASIS; bone remodeling; SPARC; TUMORIGENESIS

Sensory neurons and osteoblasts: Close partners in a microfluidic platform - Neto, E.; Alves, C.J.; Sousa, D.M.; Alencastre, I.S.; Lourenço, A.H.; Leitão, L.; Ryu, H.R.; Jeon, N.L.; Fernandes, R.; Aguiar, P.; Almeida, R.D.; Lamghari, M. (Integrative Biology (United Kingdom), 2014)
Innervation has proven to be critical in bone homeostasis/regeneration due to the effect of soluble factors, produced by nerve fibers, associated with changes in the activity of bone cells. Thus, in this study, we have established and characterized a coculture system comprising sensory neurons and osteoblasts to mimic the in vivo scenario where nerve fibers can be found in a bone microenvironment. Embryonic or adult primary dorsal root ganglion (DRG) and MC3T3-E1 osteoblastic cells were cocultured in compartmentalized microfluidic platforms and morphological and functional tests were performed. The time of adhesion and readout of axonal outgrowth were improved by the alignment of DRG with the axis of microgrooves, which showed to be a crucial step for the designed experiments. Cocultures of entire DRG from adult origin with osteoblasts were performed, showing extended DRG projections towards the axonal compartment, reaching osteoblastic cells. Immunocytochemistry showed that the neurites present within the osteoblastic compartment were immunoreactive to synapsin and calcitonin gene-related peptide suggesting the presence of specialized structures involved in this crosstalk. This evidence was further confirmed by electron microscopy where varicosities were detected as well as electron dense structures in neurite membranes. Aiming to mimic the properties of tissue extracellular matrices, MC3T3-E1 cells were seeded in the axonal side upon laminin, collagen or within 3D functionalized alginate matrices and axonal outgrowth was clearly observed. In order to analyze and quantify data with reproducible image analysis, a semi-automated algorithm was also developed. The collagen and laminin substrates displayed a higher amount of axons reaching the axonal side. Overall, the established method revealed to be a suitable tool to study the interaction between the peripheral nervous system and bone cells in different contexts mimicking the in vivo scenario. © 2014 the Partner Organisations 2014.
Cited By (since 1996):2Export Date: 21 November 2014

Splice-correcting oligonucleotides restore BTK function in X-linked agammaglobulinemia model - Bestas, B.; Moreno, P.M.D.; Blomberg, K. E. M.; Mohammad, D. K.; Saleh, A. F.; Sutlu, T.; Nordin, J. Z.; Guterstam, P.; Gustafsson, M. O.; Kharazi, S.; Piatosa, B.; Roberts, T. C.; et al. (Journal of Clinical Investigation, 2014)
Bestas, Burcu Moreno, Pedro M. D. Blomberg, K. Emelie M. Mohammad, Dara K. Saleh, Amer F. Sutlu, Tolga Nordin, Joel Z. Guterstam, Peter Gustafsson, Manuela O. Kharazi, Shabnam Piatosa, Barbara Roberts, Thomas C. Behlke, Mark A. Wood, Matthew J. A. Gait, Michael J. Lundin, Karin E. El Andaloussi, Samir Mansson, Robert Berglof, Anna Wengel, Jesper Smith, C. I. Edvard

Stability study perspective of the effect of freeze-drying using cryoprotectants on the structure of insulin loaded into PLGA nanoparticles - Fonte, P.; Soares, S.; Sousa, F.; Costa, A.; Seabra, V.; Reis, S.; Sarmento, B. (Biomacromolecules, 2014)
This work aimed to evaluate the influence of a freeze-drying process using different cryoprotectants on the structure of insulin loaded into poly(lactic-co-glycolic acid) (PLGA) nanoparticles and to assess the stability of these nanoparticles upon 6 months of storage following ICH guidelines. Insulin-loaded PLGA nanoparticles with a size around 450 nm were dehydrated using a standard freeze-drying cycle, using trehalose, glucose, sucrose, fructose, and sorbitol at 10% (w/v) as cryoprotectants. All formulations, except those nonadded of cryoprotectant and added with trehalose, collapsed after freeze-drying. The addition of cryoprotectants increased the nanoparticles stability upon storage. FTIR results showed that insulin maintained its structure after encapsulation in about 88%, decreasing to 71% after freeze-drying. The addition of cryoprotectants prior to freeze-drying increased insulin structural stability an average of up to 79%. Formulations collapsed after freeze-drying showed better protein stabilization upon storage, in special sorbitol added formulation, preserving 76, 80, and 78% of insulin structure at 4 °C, 25 °C/60% RH, and 40 °C/75% RH, respectively. Principal component analysis also showed that the sorbitol-added formulation showed the most similar insulin structural modifications among the tested storage conditions. These findings suggested that regarding nanoparticles stability, cryoprotectants are versatile to be used in a standard freeze-drying, however they present different performances on the stabilization of the loaded protein. Thus, on the freeze-drying of the nanoparticles field, this work gives rise to the importance of the process of optimization, searching for a balance between a good obtainable cake with an optimal structural stabilization of the loaded protein.

Study of the isoflavone content of different extracts of Medicago spp. as potential active ingredient - Rodrigues, F.; Almeida, I.; Sarmento, B.; Amaral, M.H.; Oliveira, M.B.P.P. (Industrial Crops and Products, 2014)
This study focuses on the isoflavones composition of different extracts of Medicago species (M. minima, M. tornata, M. truncatula, M. rigidula, M. scutelata, M. segitalis and M. sativa), a leguminous crop used as animal feeding. There are some research studies on the isoflavones composition of Medicago sativa, but no comprehensive profile of isoflavones has been reported for these other six species. In this work, two glycosides (daidzin and genistin) and six aglycones (daidzein, glycitein, genistein, formononetin, prunetin and biochanin A) were determined by high performance liquid chromatography (HPLC/DAD) in three different extracts of these species: aqueous, hydroalcoholic and alcoholic. In all samples genistin, daidzein and genistein were the most abundant isoflavone compounds. The highest concentration of genistin was observed in the extracts of M. scutelata (5.2 and 9.6. mg/kg. db, respectively, for hydroalcoholic and alcoholic extract), in amounts 2-4.5-fold higher than the other samples evaluated. Daidzein is also present in high amounts in M. scutelata (19.2. mg/kg. db, alcoholic extract). Genistein is detected in several species at concentrations ranging from 0.7 (aqueous extract of M. tornata) to 16.1. mg/kg. db (alcoholic extract of M. scutelata). In terms of total isoflavones content per species, results showed significant differences between M. rigidula and M. sativa, considering all type of solvents, being the highest and the lowest one, respectively. In a general way, the extractability of compounds significantly increased from aqueous to alcoholic extracts. The study demonstrates that some Medicago species possess an excellent potential as a source of these health promoting bioactive compounds. © 2014 Elsevier B.V.
Keywords: By-product; Daidzein; Genistein; Genistin; Isoflavones; Medicago

Adsorbed fibrinogen leads to improved bone regeneration and correlates with differences in the systemic immune response - Santos, S.G.; Lamghari, M.; Almeida, C.R.; Oliveira, M.I.; Neves, N.; Ribeiro, A.C.; Barbosa, J.N.; Barros, R.; Maciel, J.; Martins, M.C.L.; Gonçalves, R.M.; Barbosa, M.A. (Acta Biomaterialia, 2013)

Assessing the physical-chemical properties and stability of dapivirine-loaded polymeric nanoparticles - Das Neves, J.; Amiji, M.; Bahia, M.F.; Sarmento, B. (International Journal of Pharmaceutics, 2013)

Automatic lane segmentation in TLC images using the continuous wavelet transform - Moreira, B.; Sousa, A.; Mendonça, A.M.; Campilho, A. (Computational and Mathematical Methods in Medicine, 2013)

Automatic localization of the optic disc by combining vascular and intensity information - Mendonça, A.M.; Sousa, A.; Mendonça, L.; Campilho, A. (Computerized Medical Imaging and Graphics, 2013)

Brain targeting effect of camptothecin-loaded solid lipid nanoparticles in rat after intravenous administration - Martins, S.M.; Sarmento, B.; Nunes, C.; Lúcio, M.; Reis, S.; Ferreira, D.C. (European Journal of Pharmaceutics and Biopharmaceutics, 2013)

Cetuximab conjugated O-carboxymethyl chitosan nanoparticles for targeting EGFR overexpressing cancer cells - Maya, S.; Kumar, L.G.; Sarmento, B.; Sanoj Rejinold, N.; Menon, D.; Nair, S.V.; Jayakumar, R. (Carbohydrate Polymers, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Development and validation method for simultaneous quantification of phenolic compounds in natural extracts and nanosystems - Da Silva, S.B.; Oliveira, A.; Ferreira, D.; Sarmento, B.; Pintado, M. (Phytochemical Analysis, 2013)

Development of bis-locked nucleic acid (bisLNA) oligonucleotides for efficient invasion of supercoiled duplex DNA - Moreno, P.M.D.; Geny, S.; Pabon, Y.V.; Bergquist, H.; Zaghloul, E.M.; Rocha, C.S.J.; Oprea, I.I.; Bestas, B.; Andaloussi, S.E.; Jørgensen, P.T.; Pedersen, E.B.; Lundin, K.E.; et al. (Nucleic Acids Research, 2013)
Cited By (since 1996):2Export Date: 12 December 2013Source: Scopus

Development of PLGA-mannosamine nanoparticles as oral protein carriers - Alonso-Sande, M.; Des Rieux, A.; Fievez, V.; Sarmento, B.; Delgado, A.; Evora, C.; Remuñán-López, C.; Préat, V.; Alonso, M.J. (Biomacromolecules, 2013)

E-cadherin and adherens-junctions stability in gastric carcinoma: Functional implications of glycosyltransferases involving N-glycan branching biosynthesis, N-acetylglucosaminyltransferases III and v - Pinho, S.S.; Figueiredo, J.; Cabral, J.; Carvalho, S.; Dourado, J.; Magalhães, A.; Gärtner, F.; Mendonça, A.M.; Isaji, T.; Gu, J.; Carneiro, F.; Seruca, R.; et al. (Biochimica et Biophysica Acta - General Subjects, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Effect of freeze-drying, cryoprotectants and storage conditions on the stability of secondary structure of insulin-loaded solid lipid nanoparticles - Soares, S.; Fonte, P.; Costa, A.; Andrade, J.; Seabra, V.; Ferreira, D.; Reis, S.; Sarmento, B. (International Journal of Pharmaceutics, 2013)

Endothelialization of chitosan porous conduits via immobilization of a recombinant fibronectin fragment (rhFNIII7-10) - Amaral, I.F.; Neiva, I.; Ferreira da Silva, F.; Sousa, S.R.; Piloto, A.M.; Lopes, C.D.F.; Barbosa, M.A.; Kirkpatrick, C.J.; Pêgo, A.P. (Acta Biomaterialia, 2013)

Establishment of a triple co-culture in vitro cell models to study intestinal absorption of peptide drugs - Antunes, F.; Andrade, F.; Araújo, F.; Ferreira, D.; Sarmento, B. (European Journal of Pharmaceutics and Biopharmaceutics, 2013)
Cited By (since 1996):4Export Date: 12 December 2013Source: Scopus

Fibrinogen promotes resorption of chitosan by human osteoclasts - Torres, A.L.; Santos, S.G.; Oliveira, M.I.; Barbosa, M.A. (Acta Biomaterialia, 2013)

High biocompatibility and improved osteogenic potential of novel Ca-P/titania composite scaffolds designed for regeneration of load-bearing segmental bone defects - Cunha, C.; Sprio, S.; Panseri, S.; Dapporto, M.; Marcacci, M.; Tampieri, A. (Journal of Biomedical Materials Research - Part A, 2013)

Highly focalised thermotherapy using a ferrimagnetic cement in the treatment of a melanoma mouse model by low temperature hyperthermia - Portela, A.; Vasconcelos, M.; Fernandes, M.H.; Garcia, M.; Silva, A.; Gabriel, J.; Gartner, F.; Amorim, I.; Cavalheiro, J. (International Journal of Hyperthermia, 2013)
Cited By (since 1996):2Export Date: 12 December 2013Source: Scopus

Hyaluronic acid / chitosan multilayer coatings on neuronal implants for localized delivery of siRNA nanoplexes - Hartmann, H.; Hossfeld, S.; Schlosshauer, B.; Mittnacht, U.; Pêgo, A.P.; Dauner, M.; Doser, M.; Stoll, D.; Krastev, R. (Journal of Controlled Release, 2013)

Hydrolyzed galactomannan-modified nanoparticles and flower-like polymeric micelles for the active targeting of rifampicin to macrophages - Moretton, M.A.; Chiappetta, D.A.; Andrade, F.; Das Neves, J.; Ferreira, D.; Sarmento, B.; Sosnik, A. (Journal of Biomedical Nanotechnology, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

The importance of antimicrobial peptides and their potential for therapeutic use in ophthalmology - Silva, N.C.; Sarmento, B.; Pintado, M. (International Journal of Antimicrobial Agents, 2013)

In vitro and Ex Vivo evaluation of polymeric nanoparticles for vaginal and rectal delivery of the anti-HIV drug dapivirine - Das Neves, J.; Araújo, F.; Andrade, F.; Michiels, J.; Ariën, K.K.; Vanham, G.; Amiji, M.; Bahia, M.F.; Sarmento, B. (Molecular Pharmaceutics, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Information-based measure of disagreement for more than two observers: A useful tool to compare the degree of observer disagreement - Henriques, T.; Antunes, L.; Bernardes, J.; Matias, M.; Sato, D.; Costa-Santos, C. (BMC Medical Research Methodology, 2013)

Keratins and lipids in ethnic hair - Cruz, C.F.; Fernandes, M.M.; Gomes, A.C.; Coderch, L.; Martí, M.; Méndez, S.; Gales, L.; Azoia, N.G.; Shimanovich, U.; Cavaco-Paulo, A. (International Journal of Cosmetic Science, 2013)
Cited By (since 1996):3Export Date: 12 December 2013Source: Scopus

Loss of WNK2 expression by promoter gene methylation occurs in adult gliomas and triggers Rac1-mediated tumour cell invasiveness - Moniz, S.; Martinho, O.; Pinto, F.; Sousa, B.; Loureiro, C.; Oliveira, M.J.; Moita, L.F.; Honavar, M.; Pinheiro, C.; Pires, M.; Lopes, J.M.; Jones, C.; et al. (Human Molecular Genetics, 2013)
Cited By (since 1996):2Export Date: 12 December 2013Source: ScopusArt. No.: dds405

Macrophages stimulate gastric and colorectal cancer invasion through EGFR Y1086, c-Src, Erk1/2 and Akt phosphorylation and smallGTPase activity - Cardoso, A.P.; Pinto, M.L.; Pinto, A.T.; Oliveira, M.I.; Pinto, M.T.; Gonçalves, R.; Relvas, J.B.; Figueiredo, C.; Seruca, R.; Mantovani, A.; Mareel, M.; Barbosa, M.A.; et al. (Oncogene, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: ScopusArticle in Press

Medicago spp. extracts as promising ingredients for skin care products - Rodrigues, F.; Palmeira-de-Oliveira, A.; Das Neves, J.; Sarmento, B.; Amaral, M.H.; Oliveira, M.B. (Industrial Crops and Products, 2013)

Minimum error entropy classification - Marques De Sá, J.P.; Silva, L.M.A.; Santos, J.M.F.; Alexandre, L.A. (Studies in Computational Intelligence, 2013)

Month of birth and risk of multiple sclerosis in a Portuguese population - Barros, P.; De Sá, J.M.; Sá, M.J. (Clinical Neurology and Neurosurgery, 2013)

Nanotechnology and pulmonary delivery to overcome resistance in infectious diseases - Andrade, F.; Rafael, D.; Videira, M.; Ferreira, D.; Sosnik, A.; Sarmento, B. (Advanced Drug Delivery Reviews, 2013)

Neuropeptide y modulates fracture healing through Y1 receptor signaling - Sousa, D.M.; McDonald, M.M.; Mikulec, K.; Peacock, L.; Herzog, H.; Lamghari, M.; Little, D.G.; Baldock, P.A. (Journal of Orthopaedic Research, 2013)

A novel bioactive peptide: Assessing its activity over murine neural stem cells and its potential for neural tissue engineering - Caprini, A.; Silva, D.; Zanoni, I.; Cunha, C.; Volontè, C.; Vescovi, A.; Gelain, F. (New Biotechnology, 2013)

Overexpression of tumour-associated carbohydrate antigen sialyl-Tn in advanced bladder tumours - Ferreira, J.A.; Videira, P.A.; Lima, L.; Pereira, S.; Silva, M.; Carrascal, M.; Severino, P.F.; Fernandes, E.; Almeida, A.; Costa, C.; Vitorino, R.; Amaro, T.; et al. (Molecular Oncology, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Preparation and characterization of collagen-nanohydroxyapatite biocomposite scaffolds by cryogelation method for bone tissue engineering applications - Rodrigues, S.C.; Salgado, C.L.; Sahu, A.; Garcia, M.P.; Fernandes, M.H.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part A, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Protective effects of Lavandula viridis L'Hér extracts and rosmarinic acid against H2O2-induced oxidative damage in A172 human astrocyte cell line - Costa, P.; Sarmento, B.; Gonçalves, S.; Romano, A. (Industrial Crops and Products, 2013)

Should European perinatal indicators be revisited? - Santos, J.V.; Correia, C.; Cabral, F.; Bernardes, J.; Costa-Pereira, A.; Freitas, A. (European Journal of Obstetrics Gynecology and Reproductive Biology, 2013)
Cited By (since 1996):2Export Date: 12 December 2013Source: Scopus

The smart connective tissue of echinoderms: A materializing promise for biotech applications - Barbaglio, A.; Tricarico, S.; Di Benedetto, C.; Fassini, D.; Lima, A.P.; Ribeiro, A.R.; Ribeiro, C.C.; Sugni, M.; Bonasoro, F.; Wilkie, L.; Barbosa, M.; Candia Carnevali, M.D. (Cahiers de Biologie Marine, 2013)

Sociodemographic determinants of prevalence and incidence of helicobacter pylori infection in portuguese adults - Bastos, J.; Peleteiro, B.; Barros, R.; Alves, L.; Severo, M.; de Fátima Pina, M.; Pinto, H.; Carvalho, S.; Marinho, A.; Guimarães, J.T.; Azevedo, A.; La Vecchia, C.; et al. (Helicobacter, 2013)

Towards the characterization of an in vitro triple co-culture intestine cell model for permeability studies - Araújo, F.; Sarmento, B. (International Journal of Pharmaceutics, 2013)

Automatic lane detection in chromatography images - Moreira, B.M.; Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
This paper proposes a method for automating the detection of lanes in Thin-Layer Chromatography images. Our approach includes a preprocessing step to detect the image region of interest, followed by background estimation and removal. This image is then projected onto the horizontal direction to integrate the information into a one-dimensional profile. A smoothing filter is applied to this profile and the outcome is the input of the lane detection process, which is performed in three phases. The first one aims at obtaining an initial set of candidate lanes that are further validated or removed in the second phase. The last phase is a refinement step that allows the inclusion of lanes that are not clearly distinguishable in the profile and that were not included in the initial set. The method was evaluated in 66 chromatography images and achieved values of recall, precision and F β -measure of 97.0%, 99.4% and 98.2%, respectively. © 2012 Springer-Verlag.
Conference code: 91199Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-31298-4_22Language of Original Document: EnglishCorrespondence Address: Moreira, B.M.; Instituto de Engenharia Biomédica, Universidade Do Porto, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: moreira@fe.up.ptReferences: Fried, B., Sherma, J., (1999) Thin-Layer Chromatography, , Marcel Dekker, New York;Rodrigues, L.G., Ferraz, M.J., Rodrigues, D., Pais-Vieira, M., Lima, D., Brady, R.O., Sá-Miranda, M.C., Neurophysiological behavioral and morphological abnormalities in the Fabry knockout mice (2009) Neurobiology of Disease, 33 (1), pp. 48-56; Elstein, D., Altarescu, G., Beck, M., (2010) Fabry Disease, , Springer, Heidelberg; Houck, M.M., Siegel, J.A., (2010) Fundamentals of Forensic Science, , Elsevier, Oxford; Machado, A.M.C., Campos, M.F.M., Siqueira, A.M., De Carvalho, O.S.F., An iterative algorithm for segmenting lanes in gel electrophoresis images (1997) Proc. X Brazilian Symposium on Computer Graphics and Image Processing, pp. 140-146. , October; Elder, J.K., Southern, E.M., Computer-aided analysis of one dimensional restriction fragment gels (1987) Nucleic Acid and Protein Sequence Analysis - A Practical Aproach, pp. 165-172. , Bishop, M.J., Rawlings, C.J. (eds.) IRL Press, Oxford; Bajla, I., Holländer, I., Fluch, S., Burg, K., Kollár, M., An alternative method for electrophoretic gel image analysis in the GelMaster software (2005) Computer Methods and Programs in Biomedicine, 77, pp. 209-231; Lin, C., Ching, Y., Yang, Y., An Automatic Method to Compare the Lanes in Gel Electrophoresis (GE) Images (2007) IEEE Transaction on Information Technology in Biomedicine, 11 (2), pp. 179-189; Akbari, A., Fritz, A., Jackobsen, K.S., Automatic lane detection and separation in one dimensional gel images using continuous wavelet transform (2010) The Royal Society of Chemistry, Analytical Methods, 2, pp. 1360-1371; Sousa, A.V., Aguiar, R.L., Mendonça, A.M., Campilho, A.C., Automatic Lane and Band Detection in Images of Thin Layer Chromatography (2004) LNCS, 3212, pp. 158-165. , Campilho, A.C., Kamel, M.S. (eds.) ICIAR 2004. Springer, Heidelberg; Sotaquira, M., On the use of distance maps in the analysis of 1D DNA gel images (2009) ICDIP 2009: Proceedings of the International Conference on Digital Image Processing, pp. 172-176. , IEEE Computer Society; Barrantes, P., Alvarado, P., Lane Detection on Gel Electrophoresis Images using Active Shape Models (2011) Proc. of the Conference on Technologies for Sustainable Development, TSD 2011, pp. 43-46. , February; Mendonça, A.M., Sousa, A.V., Sá-Miranda, M.C., Campilho, A.C., Automatic segmentation of chromatographic images for region of interest delineation (2011) Proc. SPIE, 7962, pp. 79623B1-79623B7; Chau, F., Liang, Y., Gao, J., Shao, X., (2004) Chemometrics - from Basics to Wavelet Transform, , John Wiley & Sons, New Jersey; Press, W.H., Flannery, B.P., Teukolsky, S.A., Vetterling, W.T., (1992) Numerical Recipes in C: The Art of Scientific Computing, , Syndicate of the University of Cambridge; Soille, P., Jones, C.D., Smith, A.B., Roberts, E.F., (2004) Morphological Image Analysis - Principles and Applications, , Springer; Visa, S., Ralescu, A., Learning Imbalanced and Overlapping Classes using Fuzzy Sets Workshop on Learning from Imbalanced Datasets II, ICML (2003)
Keywords: Background estimation; Bio-medical image processing; Biomedical image processing; Chromatography; Chromatography images; Computer aided diagnosis; Image analysis; Image regions; Lane detection; Pre-processing step; Refinement step; Second phase; Smoothing filters; Three phasis

Automatic localization of the optic disc in retinal images based on the entropy of vascular directions - Mendonça, A.M.; Cardoso, F.; Sousa, A.V.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
This paper proposes an automatic method for estimating the location of the optic disc in color images of the retina. The proposed methodology is founded in a new concept, the entropy of vascular directions, which proved to be a reliable measure for assessing the convergence of vessels around an image point. To improve the robustness of the method, the search for the maximum value of entropy is restricted to image areas with high intensity. This new method was evaluated in two publicly available databases, containing both normal and pathological images, and was able to obtain a valid location for the optic disc in 115 out of the 121 images of the two datasets. © 2012 Springer-Verlag.
Conference code: 91199Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-31298-4_50Language of Original Document: EnglishCorrespondence Address: Mendonça, A.M.; Instituto de Engenharia Biomédica, Universidade Do Porto, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: amendon@fe.up.ptReferences: Jelinek, H., Cree, M., (2010) Automated Image Detection of Retinal Pathology, , CRC Press, Taylor & Francis Group, Boca Raton;Couper, D.J., Klein, R., Hubbard, L.D., Wong, T.Y., Sorlie, P., Cooper, L.S., Brothers, R.J., Nieto, F.J., Reliability of Retinal Photography in the Assessment of Retinal Microvascular Characteristics: The Atherosclerosis Risk in Communities Study (2002) American Journal of Ophthalmology, 133 (1), pp. 78-88; Sinthanayothin, C., Boyce, J.F., Cook, H.L., Williamson, T.H., Automated localization of the optic disc, fovea, and retinal blood vessels from digital colour fundus images (1999) Br. J. Ophthalmol., 83, pp. 902-910; Aquino, A., Gegúndez-Arias, M.E., Marin, D., Detecting the Optic Disc Boundary in Digital Fundus Images Using Morphological, Edge Detection and Feature Extraction Techniques (2010) IEEE Trans. Medical Imaging, 29 (11), pp. 1860-1869; Aquino, A., Gegúndez-Arias, M.E., Marin, D., Automated Optic Disc Detection in Retinal Images of Patients with Diabetic Retinopathy and Risk of Macular Edema (2012) Int. J. of Biological and Life Sciences, 8 (2), pp. 87-92; Lalonde, M., Beaulieu, M., Gagnon, L., Fast and Robust Optic Disc Detection Using Pyramidal Decomposition and Hausdorff-based Template Matching (2001) IEEE Trans. Medical Imaging, 20 (11), pp. 1193-1200; Osareh, A., Mirmehdi, M., Thomas, B., Markham, R., Classification and Localisation of Diabetic-Related Eye Disease (2002) LNCS, 2353, pp. 502-516. , Heyden, A., Sparr, G., Nielsen, M., Johansen, P. (eds.) ECCV 2002. Springer, Heidelberg; Lowell, J., Hunter, A., Steel, D., Basu, A., Ryder, R., Fletcher, E., Kennedy, L., Optic Nerve head Segmentation (2004) IEEE Trans. Medical Imaging, 23 (2), pp. 256-264; Abdel-Ghafar, R.A., Morris, T., Progress towards automated detection and characterization of the optic disc in glaucoma and diabetic retinopathy (2007) Medical Informatics and the Internet in Medicine, 32 (1), pp. 19-25; Hoover, A., Glodbaum, M., Locating the Optic Nerve in a Retinal Image Using the Fuzzy Convergence of the Blood Vessels (2003) IEEE Trans. Medical Imaging, 22 (8), pp. 951-958; Foracchia, M., Grisan, E., Ruggeri, A., Detection of Optic Disc in Retinal Images by Means of a Geometrical Model of Vessel Structure (2004) IEEE Trans. Medical Imaging, 23 (10), pp. 1189-1195; Haar, F., (2005) Automatic Localization of the Optic Disc in Digital Colour Images of the Human Retina, , Msc Thesis, University of Utrecht; Youssif, A., Ghalwash, A.Z., Ghoneim, A., Optic Disc Detection from Normalized Digital Fundus Images by Means of a Vessels' Direction Matched Filter (2008) IEEE Trans. Medical Imaging, 27 (1), pp. 11-18; Niemeijer, M., Abràmoff, M.D., Van Ginneken, B., Fast detection of the optic disc and fovea in color fundus photographs (2009) Medical Image Analysis, 13, pp. 859-870; Xu, X., Gravin, M.K., Abràmoff, M.D., Reinhardt, J.M., Simultaneous Automatic Detection of the Optic Disc and Fovea on Fundus Photographs (2011) Proc. SPIE Medical Imaging 2011: Image Processing, 7962, pp. 7962T. , Dawant, B.M., Haynor, D.R. (eds.) SPIE; http://www.isi.uu.nl/Research/Databases/DRIVEhttp://www.ces.clemson.edu/~ahoover/stare, The STARE projectMendonça, A., Campilho, A., Segmentation of Retinal Blood Vessels by Combining the Detection of Centerlines and Morphological Reconstruction (2006) IEEE Trans. Medical Imaging, 25 (9), pp. 1200-1213; Chaudhuri, S., Chattererjee, S., Katz, N., Glodbaum, M., Detection of blood Vessels in Retinal Images using Two-Dimensional Matched Filters (1989) IEEE Trans. Medical Imaging, 28 (3), pp. 263-269
Keywords: Automatic localization; Automatic method; Color images; Data sets; entropy; High intensity; Image analysis; Image points; Maximum values; Ophthalmology; optic disc; Pathological images; Retinal image; Retinal image analysis; vessel segmentation

Brain delivery of camptothecin by means of solid lipid nanoparticles: Formulation design, in vitro and in vivo studies - Martins, S.; Tho, I.; Reimold, I.; Fricker, G.; Souto, E.; Ferreira, D.; Brandl, M. (International Journal of PharmaceuticsInt. J. Pharm., 2012)
For the purpose of brain delivery upon intravenous injection, formulations of camptothecin-loaded solid lipid nanoparticles (SLN), prepared by hot high pressure homogenisation, were designed. Incorporation of camptothecin in the hydrophobic and acidic environment of SLN matrix was chosen to stabilise the lactone ring, which is essential for its antitumour activity, and for avoiding premature loss of drug on the way to target camptothecin to the brain.A multivariate approach was used to assess the influence of the qualitative and quantitative composition on the physicochemical properties of camptothecin-loaded SLN in comparison to plain SLN. Mean particle sizes of ≤200. nm, homogenous size distributions and high encapsulation efficiencies (>90%) were achieved for the most suitable formulations. In vitro release studies in plasma, showed a prolonged release profile of camptothecin from SLN, confirming the physical stability of the particles under physiological pH. A higher affinity of the SLN to the porcine brain capillary endothelial cells (BCEC) was shown in comparison to macrophages. MTT studies in BCEC revealed a moderate decrease in the cell viability of camptothecin, when incorporated in SLN compared to free camptothecin in solution. In vivo studies in rats showed that fluorescently labelled SLN were detected in the brain after i.v. administration. This study indicates that the camptothecin-loaded SLN are a promising drug brain delivery system worth to explore further for brain tumour therapy. © 2012 Elsevier B.V.
Keywords: Brain capillary endothelial cells (BCEC); Brain delivery; Camptothecin; Multivariate analysis; Solid lipid nanoparticles (SLN); Surfactants

Cancer syndromes and therapy by stop-codon readthrough - Bordeira-Carriço, R.; Pêgo, A.P.; Santos, M.; Oliveira, C. (Trends in Molecular MedicineTrends Mol. Med., 2012)
Several hereditary cancer syndromes are associated with nonsense mutations that create premature termination codons (PTC). Therapeutic strategies involving readthrough induction partially restore expression of proteins with normal function from nonsense-mutated genes, and small molecules such as aminoglycosides and PTC124 have exhibited promising results for treating patients with cystic fibrosis and Duchenne muscular dystrophy. Transgenic expression of suppressor-tRNAs and depleting translation termination factors are, among others, potential strategies for treating PTC-associated diseases. In this review, the potential of using readthrough strategies as a therapy for cancer syndromes is discussed, and we consider the effect of nonsense-mediated decay and other factors on readthrough efficiency. © 2012 Elsevier Ltd.
Keywords: Aminoglycosides; Hereditary cancer syndromes; Nonsense-mediated decay (NMD); Nonsense-suppression; Premature termination codon (PTC); PTC124; Readthrough; Suppressor-tRNA

Cell-based in vitro models for predicting drug permeability - Sarmento, B.; Andrade, F.; Da Silva, S.B.; Rodrigues, F.; Das Neves, J.; Ferreira, D. (Expert Opinion on Drug Metabolism and ToxicologyExpert Opin. Drug Metab. Toxicol., 2012)
In vitro cell models have been used to predict drug permeation in early stages of drug development, since they represent an easy and reproducible method, allowing the tracking of drug absorption rate and mechanism, with an advantageous costbenefit ratio. Such cell-based models are mainly composed of immortalized cells with an intrinsic ability to grow in a monolayer when seeded in permeable supports, maintaining their physiologic characteristics regarding epithelium cell physiology and functionality. Areas covered: This review summarizes the most important intestinal, pulmonary, nasal, vaginal, rectal, ocular and skin cell-based in vitro models for predicting the permeability of drugs. Moreover, the similitude between in vitro cell models and in vivo conditions are discussed, providing evidence that each model may provisionally resemble different drug absorption route. Expert opinion: Despite the widespread use of in vitro cell models for drug permeability and absorption evaluation purposes, a detailed study on the properties of these models and their in vitroin vivo correlation compared with human data are required to further use in order to consider a future drug discovery optimization and clinical development. © 2012 Informa UK, Ltd.
Keywords: Animals; Caco-2 Cells; carcinoma cell; cell differentiation; cell growth; Cell Line; Cell Membrane Permeability; cell models; cell proliferation; cell strain CACO 2; cell type; Cells; conjunctiva; drug absorption; drug bioavailability; drug delivery system; drug penetration; drug screening; drug transport; epithelium cell; Eye; human; Humans; in vitro models; in vitro study; in vitroin vivo correlation; Intestinal Absorption; intestinal mucosa; intestine cell; Intestines; Lung; lung alveolus cell; Models, Biological; molecular weight; nasal cell; nonhuman; ocular cell; permeability; Pharmaceutical Preparations; rectal cell; review; Skin; skin cell; vaginal cell

Chitosan drives anti-inflammatory macrophage polarisation and pro-inflammatory dendritic cell stimulation. - Oliveira, M.I.; Santos, S.G.; Oliveira, M.J.; Torres, A.L.; Barbosa, M.A. (European cells & materialsEur Cell Mater, 2012)
Macrophages and dendritic cells (DC) share the same precursor and play key roles in immunity. Modulation of their behaviour to achieve an optimal host response towards an implanted device is still a challenge. Here we compare the differentiation process and polarisation of these related cell populations and show that they exhibit different responses to chitosan (Ch), with human monocyte-derived macrophages polarising towards an anti-inflammatory phenotype while their DC counterparts display pro-inflammatory features. Macrophages and DC, whose interactions with biomaterials are frequently analysed using fully differentiated cells, were cultured directly on Ch films, rather than exposed to the polymer after complete differentiation. Ch was the sole stimulating factor and activated both macrophages and DC, without leading to significant T cell proliferation. After 10 d on Ch, macrophages significantly down-regulated expression of pro-inflammatory markers, CD86 and MHCII. Production of pro-inflammatory cytokines, particularly TNF-α, decreased with time for cells cultured on Ch, while anti-inflammatory IL-10 and TGF-β1, significantly increased. Altogether, these results suggest an M2c polarisation. Also, macrophage matrix metalloproteinase activity was augmented and cell motility was stimulated by Ch. Conversely, DC significantly enhanced CD86 expression, reduced IL-10 secretion and increased TNF-α and IL-1β levels. Our findings indicate that cells with a common precursor may display different responses, when challenged by the same biomaterial. Moreover, they help to further comprehend macrophage/DC interactions with Ch and the balance between pro- and anti-inflammatory signals associated with implant biomaterials. We propose that an overall pro-inflammatory reaction may hide the expression of anti-inflammatory cytokines, likely relevant for tissue repair/regeneration.
Keywords: antibody specificity; Antigens, CD86; article; Biocompatible Materials; biomaterial; biosynthesis; CD86 antigen; Cell culture; cell differentiation; cell motion; Cell Movement; Cells, Cultured; chitosan; cytology; dendritic cell; Dendritic Cells; drug effect; flow cytometry; Histocompatibility Antigens Class II; HLA antigen class 2; human; Humans; IL10 protein, human; immunology; interleukin 10; Interleukin-10; macrophage; Macrophages; metabolism; monocyte; Monocytes; Organ Specificity; transforming growth factor beta1; tumor necrosis factor alpha; Tumor Necrosis Factor-alpha

E-cadherin dysfunction in gastric cancer - Cellular consequences, clinical applications and open questions - Carneiro, P.; Fernandes, M.S.; Figueiredo, J.; Caldeira, J.; Carvalho, J.; Pinheiro, H.; Leite, M.; Melo, S.; Oliveira, P.; Simões-Correia, J.; Oliveira, M.J.; Carneiro, F.; et al. (FEBS LettersFEBS Lett., 2012)
E-cadherin plays a major role in cell-cell adhesion and inactivating germline mutations in its encoding gene predispose to hereditary diffuse gastric cancer. Evidence indicates that aside from its recognized role in early tumourigenesis, E-cadherin is also pivotal for tumour progression, including invasion and metastization. Herein, we discuss E-cadherin alterations found in a cancer context, associated cellular effects and signalling pathways, and we raise new key questions that will impact in the management of GC patients and families. © 2012 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
Keywords: Adhesion; Cadherins; cancer growth; cancer invasion; cancer patient; cancer susceptibility; cell adhesion; complex formation; conference paper; E-cadherin; embryo development; endocytosis; epigenetics; epithelial mesenchymal transition; Gastric cancer; gene mutation; gene silencing; genetic susceptibility; Germ-Line Mutation; HDGC; Helicobacter infection; Helicobacter Infections; Helicobacter pylori; histone deacetylase inhibitor; human; Humans; Invasion; metastasis; molecular pathology; nonhuman; priority journal; protein analysis; protein depletion; protein expression; protein function; protein structure; regulatory mechanism; signal transduction; Signalling; stomach cancer; stomach carcinogenesis; Stomach Neoplasms; Tumour; uvomorulin

The effect of octadecyl chain immobilization on the hemocompatibility of poly (2-hydroxyethyl methacrylate) - Fischer, M.; Baptista, C.P.; Gonçalves, I.C.; Ratner, B.D.; Sperling, C.; Werner, C.; Martins, C.L.; Barbosa, M.A. (BiomaterialsBiomaterials, 2012)
Albumin-scavenging surfaces decorated with n-alkyl chains represent an established strategy for blood-contacting applications. To evaluate this concept, a set of poly (2-hydroxyethyl methacrylate) (pHEMA) films modified with different amounts of octadecyl isocyanate (C18) was investigated in an in vitro hemocompatibility assay using freshly drawn human whole blood. In addition, the hydrogel materials were thoroughly characterized with respect to changes in wettability and elasticity, which accompanied the gradual chemical modification of pHEMA. An increase of the surface C18 content induced enhanced hydrophobicity and stiffness. Immobilization of C18 chains was found to substantially reduce the coagulation activation and the complement activation by the pHEMA films. Platelet adhesion and degranulation (PF4 release) were similar on the modified and the unmodified pHEMA. Platelet adhesion to pHEMA hydrogels was lower than the polytetrafluoroethylene reference. We conclude that the immobilization of octadecyl chains improved the hemocompatibility of pHEMA materials under conditions that might be encountered in low shear blood flow. © 2012 Elsevier Ltd.
Keywords: Adhesion; Albumin; article; Biological materials; Biomaterials; Blood; Blood flow; Chemical modification; Coagulation; controlled study; Degranulation; Elasticity; Haemocompatibility; Hemocompatibility; human; hydrogel; in vitro study; In-vitro; isocyanate; Octadecyl; octadecyl isocyanate; PHEMA; Platelet adhesion; Platelets; Poly(2-hydroxyethyl methacrylate); PolyHEMA; polymacon; priority journal; Protein adsorption; thrombocyte adhesion; unclassified drug; wettability; Whole blood

Endothelialization of chitosan porous conduits via immobilization of a recombinant fibronectin fragment (rhFNIII 7-10) - Amaral, I.F.; Neiva, I.; Ferreira da Silva, F.; Sousa, S.R.; Piloto, A.M.; Lopes, C.D.F.; Barbosa, M.A.; Kirkpatrick, C.J.; Pêgo, A.P. (Acta BiomaterialiaActa Biomater., 2012)
The present study aimed to develop a pre-endothelialized chitosan (CH) porous hollowed scaffold for application in spinal cord regenerative therapies. CH conduits with different degrees of acetylation (DA; 4% and 15%) were prepared, characterized (microstructure, porosity and water uptake) and functionalized with a recombinant fragment of human fibronectin (rhFNIII 7-10). Immobilized rhFNIII 7-10 was characterized in terms of amount ( 125I-radiolabelling), exposure of cell-binding domains (immunofluorescence) and ability to mediate endothelial cell (EC) adhesion and cytoskeletal rearrangement. Functionalized conduits revealed a linear increase in immobilized rhFNIII 7-10 with rhFNIII 7-10 concentration, and, for the same concentration, higher amounts of rhFNIII 7-10 on DA 4% compared with DA 15%. Moreover, rhFNIII 7-10 concentrations as low as 5 and 20 μg ml
Keywords: Protein conformation; Protein radiolabelling; Spinal cord injury; Surface grafting; Three-dimensional scaffolds

Epithelial E- and P-cadherins: Role and clinical significance in cancer - Paredes, J.; Figueiredo, J.; Albergaria, A.; Oliveira, P.; Carvalho, J.; Ribeiro, A.S.; Caldeira, J.; Costa, A.M.; Simões-Correia, J.; Oliveira, M.J.; Pinheiro, H.; Pinho, S.S.; et al. (Biochimica et Biophysica Acta - Reviews on CancerBiochim. Biophys. Acta Rev. Cancer, 2012)
E-cadherin and P-cadherin are major contributors to cell-cell adhesion in epithelial tissues, playing pivotal roles in important morphogenetic and differentiation processes during development, and in maintaining integrity and homeostasis in adult tissues. It is now generally accepted that alterations in these two molecules are observed during tumour progression of most carcinomas. Genetic or epigenetic alterations in E- and P-cadherin-encoding genes (CDH1 and CDH3, respectively), or alterations in their proteins expression, often result in tissue disorder, cellular de-differentiation, increased invasiveness of tumour cells and ultimately in metastasis. In this review, we will discuss the major properties of E- and P-cadherin molecules, its regulation in normal tissue, and their alterations and role in cancer, with a specific focus on gastric and breast cancer models. © 2012 Elsevier B.V.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: BBACEdoi: 10.1016/j.bbcan.2012.05.002Language of Original Document: EnglishCorrespondence Address: Seruca, R.; IPATIMUP, Institute of Molecular Pathology and Immunology, University of Porto, Rua Dr. Roberto Frias s/n, 4200-465 Porto, Portugal; email: rseruca@ipatimup.ptChemicals/CAS: uvomorulin, 112956-45-3Tradenames: pf 03732010References: Cavallaro, U., Christofori, G., Cell adhesion and signalling by cadherins and Ig-CAMs in cancer (2004) Nat. Rev. Cancer, 4, pp. 118-132;Gerrow, K., El-Husseini, A., Cell adhesion molecules at the synapse (2006) Front. Biosci., 11, pp. 2400-2419; Nollet, F., Kools, P., van Roy, F., Phylogenetic analysis of the cadherin superfamily allows identification of six major subfamilies besides several solitary members (2000) J. Mol. Biol., 299, pp. 551-572; Takeichi, M., Cadherins in cancer: implications for invasion and metastasis (1993) Curr. Opin. Cell Biol., 5, pp. 806-811; Pignatelli, M., Bodmer, W.F., Genetics and biochemistry of collagen binding-triggered glandular differentiation in a human colon carcinoma cell line (1988) Proc. Natl. Acad. Sci. U. S. A., 85, pp. 5561-5565; Takeichi, M., Morphogenetic roles of classic cadherins (1995) Curr. Opin. Cell Biol., 7, pp. 619-627; Shapiro, L., Fannon, A.M., Kwong, P.D., Thompson, A., Lehmann, M.S., Grubel, G., Legrand, J.F., Hendrickson, W.A., Structural basis of cell-cell adhesion by cadherins (1995) Nature, 374, pp. 327-337; Ozawa, M., Ringwald, M., Kemler, R., Uvomorulin-catenin complex formation is regulated by a specific domain in the cytoplasmic region of the cell adhesion molecule (1990) Proc. Natl. Acad. Sci. U. S. A., 87, pp. 4246-4250; Blaschuk, O.W., Sullivan, R., David, S., Pouliot, Y., Identification of a cadherin cell adhesion recognition sequence (1990) Dev. Biol., 139, pp. 227-229; Ozawa, M., Baribault, H., Kemler, R., The cytoplasmic domain of the cell adhesion molecule uvomorulin associates with three independent proteins structurally related in different species (1989) EMBO J., 8, pp. 1711-1717; Gumbiner, B.M., McCrea, P.D., Catenins as mediators of the cytoplasmic functions of cadherins (1993) J. Cell Sci. Suppl., 17, pp. 155-158; Yap, A.S., Niessen, C.M., Gumbiner, B.M., The juxtamembrane region of the cadherin cytoplasmic tail supports lateral clustering, adhesive strengthening, and interaction with p120ctn (1998) J. Cell Biol., 141, pp. 779-789; Van Aken, E., De Wever, O., Correia da Rocha, A.S., Mareel, M., Defective E-cadherin/catenin complexes in human cancer (2001) Virchows Arch., 439, pp. 725-751; Mareel, M., Oliveira, M.J., Madani, I., Cancer invasion and metastasis: interacting ecosystems (2009) Virchows Arch., 454, pp. 599-622; Makrilia, N., Kollias, A., Manolopoulos, L., Syrigos, K., Cell adhesion molecules: role and clinical significance in cancer (2009) Cancer Invest., 27, pp. 1023-1037; Bussemakers, M.J., van Bokhoven, A., Voller, M., Smit, F.P., Schalken, J.A., The genes for the calcium-dependent cell adhesion molecules P- and E-cadherin are tandemly arranged in the human genome (1994) Biochem. Biophys. Res. Commun., 203, pp. 1291-1294; Berx, G., Staes, K., van Hengel, J., Molemans, F., Bussemakers, M.J., van Bokhoven, A., van Roy, F., Cloning and characterization of the human invasion suppressor gene E-cadherin (CDH1) (1995) Genomics, 26, pp. 281-289; Jarrard, D.F., Paul, R., van Bokhoven, A., Nguyen, S.H., Bova, G.S., Wheelock, M.J., Johnson, K.R., Isaacs, W.B., P-cadherin is a basal cell-specific epithelial marker that is not expressed in prostate cancer (1997) Clin. Cancer Res., 3, pp. 2121-2128; Hubbard, T.J., Aken, B.L., Ayling, S., Ballester, B., Beal, K., Bragin, E., Brent, S., Flicek, P., Ensembl 2009 (2009) Nucleic Acids Res., 37, pp. D690-D697; Faraldo, M.L., Cano, A., The 5' flanking sequences of the mouse P-cadherin gene. Homologies to 5' sequences of the E-cadherin gene and identification of a first 215 base-pair intron (1993) J. Mol. Biol., 231, pp. 935-941; van Roy, F., Berx, G., The cell-cell adhesion molecule E-cadherin (2008) Cell. Mol. Life Sci., 65, pp. 3756-3788; Stemmler, M.P., Cadherins in development and cancer (2008) Mol. Biosyst., 4, pp. 835-850; Paredes, J., Albergaria, A., Oliveira, J.T., Jeronimo, C., Milanezi, F., Schmitt, F.C., P-cadherin overexpression is an indicator of clinical outcome in invasive breast carcinomas and is associated with CDH3 promoter hypomethylation (2005) Clin. Cancer Res., 11, pp. 5869-5877; Sakharkar, K.R., Chow, V.T., PPD-proteome profile database (2004) In Silico Biol., 4, pp. 219-223; Thomas, D.J., Rosenbloom, K.R., Clawson, H., Hinrichs, A.S., Trumbower, H., Raney, B.J., Karolchik, D., Kent, W.J., The ENCODE Project at UC Santa Cruz (2007) Nucleic Acids Res., 35, pp. D663-D667; Oliveira, P., Sanges, R., Huntsman, D., Stupka, E., Oliveira, C., Characterization of the intronic portion of cadherin superfamily members, common cancer orchestrators (2012) Eur. J. Hum. Genet.; Hosono, S., Gross, I., English, M.A., Hajra, K.M., Fearon, E.R., Licht, J.D., E-cadherin is a WT1 target gene (2000) J. Biol. Chem., 275, pp. 10943-10953; Liu, Y.N., Lee, W.W., Wang, C.Y., Chao, T.H., Chen, Y., Chen, J.H., Regulatory mechanisms controlling human E-cadherin gene expression (2005) Oncogene, 24, pp. 8277-8290; Behrens, J., Lowrick, O., Klein-Hitpass, L., Birchmeier, W., The E-cadherin promoter: functional analysis of a G.C-rich region and an epithelial cell-specific palindromic regulatory element (1991) Proc. Natl. Acad. Sci. U. S. A., 88, pp. 11495-11499; Cano, A., Perez-Moreno, M.A., Rodrigo, I., Locascio, A., Blanco, M.J., del Barrio, M.G., Portillo, F., Nieto, M.A., The transcription factor snail controls epithelial-mesenchymal transitions by repressing E-cadherin expression (2000) Nat. Cell Biol., 2, pp. 76-83; Hajra, K.M., Chen, D.Y., Fearon, E.R., The SLUG zinc-finger protein represses E-cadherin in breast cancer (2002) Cancer Res., 62, pp. 1613-1618; Perez-Moreno, M.A., Locascio, A., Rodrigo, I., Dhondt, G., Portillo, F., Nieto, M.A., Cano, A., A new role for E12/E47 in the repression of E-cadherin expression and epithelial-mesenchymal transitions (2001) J. Biol. Chem., 276, pp. 27424-27431; Comijn, J., Berx, G., Vermassen, P., Verschueren, K., van Grunsven, L., Bruyneel, E., Mareel, M., van Roy, F., The two-handed E box binding zinc finger protein SIP1 downregulates E-cadherin and induces invasion (2001) Mol. Cell, 7, pp. 1267-1278; Eger, A., Aigner, K., Sonderegger, S., Dampier, B., Oehler, S., Schreiber, M., Berx, G., Foisner, R., DeltaEF1 is a transcriptional repressor of E-cadherin and regulates epithelial plasticity in breast cancer cells (2005) Oncogene, 24, pp. 2375-2385; Peinado, H., Olmeda, D., Cano, A., Snail, Zeb and bHLH factors in tumour progression: an alliance against the epithelial phenotype? (2007) Nat. Rev. Cancer, 7, pp. 415-428; Shi, Y., Sawada, J., Sui, G., Affar el, B., Whetstine, J.R., Lan, F., Ogawa, H., Nakatani, Y., Coordinated histone modifications mediated by a CtBP co-repressor complex (2003) Nature, 422, pp. 735-738; Jamora, C., DasGupta, R., Kocieniewski, P., Fuchs, E., Links between signal transduction, transcription and adhesion in epithelial bud development (2003) Nature, 422, pp. 317-322; Vandewalle, C., Comijn, J., De Craene, B., Vermassen, P., Bruyneel, E., Andersen, H., Tulchinsky, E., Berx, G., SIP1/ZEB2 induces EMT by repressing genes of different epithelial cell-cell junctions (2005) Nucleic Acids Res., 33, pp. 6566-6578; Aigner, K., Dampier, B., Descovich, L., Mikula, M., Sultan, A., Schreiber, M., Mikulits, W., Eger, A., The transcription factor ZEB1 (deltaEF1) promotes tumour cell dedifferentiation by repressing master regulators of epithelial polarity (2007) Oncogene, 26, pp. 6979-6988; Spaderna, S., Schmalhofer, O., Wahlbuhl, M., Dimmler, A., Bauer, K., Sultan, A., Hlubek, F., Brabletz, T., The transcriptional repressor ZEB1 promotes metastasis and loss of cell polarity in cancer (2008) Cancer Res., 68, pp. 537-544; Graff, J.R., Herman, J.G., Lapidus, R.G., Chopra, H., Xu, R., Jarrard, D.F., Isaacs, W.B., Baylin, S.B., E-cadherin expression is silenced by DNA hypermethylation in human breast and prostate carcinomas (1995) Cancer Res., 55, pp. 5195-5199; Shimomura, Y., Wajid, M., Shapiro, L., Christiano, A.M., P-cadherin is a p63 target gene with a crucial role in the developing human limb bud and hair follicle (2008) Development, 135, pp. 743-753; Carroll, D.K., Carroll, J.S., Leong, C.O., Cheng, F., Brown, M., Mills, A.A., Brugge, J.S., Ellisen, L.W., P63 regulates an adhesion programme and cell survival in epithelial cells (2006) Nat. Cell Biol., 8, pp. 551-561; Faraldo, M.M., Teuliere, J., Deugnier, M.A., Birchmeier, W., Huelsken, J., Thiery, J.P., Cano, A., Glukhova, M.A., Beta-catenin regulates P-cadherin expression in mammary basal epithelial cells (2007) FEBS Lett., 581, pp. 831-836; Le, T.L., Yap, A.S., Stow, J.L., Recycling of E-cadherin: a potential mechanism for regulating cadherin dynamics (1999) J. Cell Biol., 146, pp. 219-232; Bryant, D.M., Stow, J.L., The ins and outs of E-cadherin trafficking (2004) Trends Cell Biol., 14, pp. 427-434; Hinck, L., Nathke, I.S., Papkoff, J., Nelson, W.J., Dynamics of cadherin/catenin complex formation: novel protein interactions and pathways of complex assembly (1994) J. Cell Biol., 125, pp. 1327-1340; Chen, Y.T., Stewart, D.B., Nelson, W.J., Coupling assembly of the E-cadherin/beta-catenin complex to efficient endoplasmic reticulum exit and basal-lateral membrane targeting of E-cadherin in polarized MDCK cells (1999) J. Cell Biol., 144, pp. 687-699; Lock, J.G., Stow, J.L., Rab11 in recycling endosomes regulates the sorting and basolateral transport of E-cadherin (2005) Mol. Biol. Cell, 16, pp. 1744-1755; Bryant, D.M., Kerr, M.C., Hammond, L.A., Joseph, S.R., Mostov, K.E., Teasdale, R.D., Stow, J.L., EGF induces macropinocytosis and SNX1-modulated recycling of E-cadherin (2007) J. Cell Sci., 120, pp. 1818-1828; Ling, K., Bairstow, S.F., Carbonara, C., Turbin, D.A., Huntsman, D.G., Anderson, R.A., Type I gamma phosphatidylinositol phosphate kinase modulates adherens junction and E-cadherin trafficking via a direct interaction with mu 1B adaptin (2007) J. Cell Biol., 176, pp. 343-353; Mosesson, Y., Mills, G.B., Yarden, Y., Derailed endocytosis: an emerging feature of cancer (2008) Nat. Rev. Cancer, 8, pp. 835-850; Ireton, R.C., Davis, M.A., van Hengel, J., Mariner, D.J., Barnes, K., Thoreson, M.A., Anastasiadis, P.Z., Reynolds, A.B., A novel role for p120 catenin in E-cadherin function (2002) J. Cell Biol., 159, pp. 465-476; Davis, M.A., Ireton, R.C., Reynolds, A.B., A core function for p120-catenin in cadherin turnover (2003) J. Cell Biol., 163, pp. 525-534; Xiao, K., Garner, J., Buckley, K.M., Vincent, P.A., Chiasson, C.M., Dejana, E., Faundez, V., Kowalczyk, A.P., P120-Catenin regulates clathrin-dependent endocytosis of VE-cadherin (2005) Mol. Biol. Cell, 16, pp. 5141-5151; Taniuchi, K., Nakagawa, H., Hosokawa, M., Nakamura, T., Eguchi, H., Ohigashi, H., Ishikawa, O., Nakamura, Y., Overexpressed P-cadherin/CDH3 promotes motility of pancreatic cancer cells by interacting with p120ctn and activating rho-family GTPases (2005) Cancer Res., 65, pp. 3092-3099; Paredes, J., Stove, C., Stove, V., Milanezi, F., Van Marck, V., Derycke, L., Mareel, M., Schmitt, F., P-cadherin is up-regulated by the antiestrogen ICI 182,780 and promotes invasion of human breast cancer cells (2004) Cancer Res., 64, pp. 8309-8317; Palacios, F., Price, L., Schweitzer, J., Collard, J.G., D'Souza-Schorey, C., An essential role for ARF6-regulated membrane traffic in adherens junction turnover and epithelial cell migration (2001) EMBO J., 20, pp. 4973-4986; Figueiredo, J., Simoes-Correia, J., Soderberg, O., Suriano, G., Seruca, R., ADP-ribosylation factor 6 mediates E-cadherin recovery by chemical chaperones (2011) PLoS One, 6, pp. e23188; Palacios, F., Schweitzer, J.K., Boshans, R.L., D'Souza-Schorey, C., ARF6-GTP recruits Nm23-H1 to facilitate dynamin-mediated endocytosis during adherens junctions disassembly (2002) Nat. Cell Biol., 4, pp. 929-936; Otsuki, Y., Tanaka, M., Yoshii, S., Kawazoe, N., Nakaya, K., Sugimura, H., Tumor metastasis suppressor nm23H1 regulates Rac1 GTPase by interaction with Tiam1 (2001) Proc. Natl. Acad. Sci. U. S. A., 98, pp. 4385-4390; Morishige, M., Hashimoto, S., Ogawa, E., Toda, Y., Kotani, H., Hirose, M., Wei, S., Sabe, H., GEP100 links epidermal growth factor receptor signalling to Arf6 activation to induce breast cancer invasion (2008) Nat. Cell Biol., 10, pp. 85-92; Daniel, J.M., Reynolds, A.B., Tyrosine phosphorylation and cadherin/catenin function (1997) Bioessays, 19, pp. 883-891; Palacios, F., Tushir, J.S., Fujita, Y., D'Souza-Schorey, C., Lysosomal targeting of E-cadherin: a unique mechanism for the down-regulation of cell-cell adhesion during epithelial to mesenchymal transitions (2005) Mol. Cell. Biol., 25, pp. 389-402; Fujita, Y., Krause, G., Scheffner, M., Zechner, D., Leddy, H.E., Behrens, J., Sommer, T., Birchmeier, W., Hakai, a c-Cbl-like protein, ubiquitinates and induces endocytosis of the E-cadherin complex (2002) Nat. Cell Biol., 4, pp. 222-231; Pinho, S.S., Seruca, R., Gartner, F., Yamaguchi, Y., Gu, J., Taniguchi, N., Reis, C.A., Modulation of E-cadherin function and dysfunction by N-glycosylation (2011) Cell. Mol. Life Sci., 68, pp. 1011-1020; Zhu, W., Leber, B., Andrews, D.W., Cytoplasmic O-glycosylation prevents cell surface transport of E-cadherin during apoptosis (2001) EMBO J., 20, pp. 5999-6007; Zhou, F., Su, J., Fu, L., Yang, Y., Zhang, L., Wang, L., Zhao, H., Zha, X., Unglycosylation at Asn-633 made extracellular domain of E-cadherin folded incorrectly and arrested in endoplasmic reticulum, then sequentially degraded by ERAD (2008) Glycoconj. J., 25, pp. 727-740; Liwosz, A., Lei, T., Kukuruzinska, M.A., N-glycosylation affects the molecular organization and stability of E-cadherin junctions (2006) J. Biol. Chem., 281, pp. 23138-23149; Pinho, S.S., Reis, C.A., Paredes, J., Magalhaes, A.M., Ferreira, A.C., Figueiredo, J., Xiaogang, W., Seruca, R., The role of N-acetylglucosaminyltransferase III and V in the post-transcriptional modifications of E-cadherin (2009) Hum. Mol. Genet., 18, pp. 2599-2608; Pinho, S.S., Oliveira, P., Cabral, J., Carvalho, S., Huntsman, D., Gartner, F., Seruca, R., Oliveira, C., Loss and recovery of Mgat3 and GnT-III mediated E-cadherin N-glycosylation is a mechanism involved in epithelial-mesenchymal-epithelial transitions (2012) PLoS One, 7, pp. e33191; Osumi, D., Takahashi, M., Miyoshi, E., Yokoe, S., Lee, S.H., Noda, K., Nakamori, S., Taniguchi, N., Core fucosylation of E-cadherin enhances cell-cell adhesion in human colon carcinoma WiDr cells (2009) Cancer Sci., 100, pp. 888-895; Takeichi, M., Functional correlation between cell adhesive properties and some cell surface proteins (1977) J. Cell Biol., 75, pp. 464-474; Hyafil, F., Morello, D., Babinet, C., Jacob, F., A cell surface glycoprotein involved in the compaction of embryonal carcinoma cells and cleavage stage embryos (1980) Cell, 21, pp. 927-934; Ogou, S., Okada, T.S., Takeichi, M., Cleavage stage mouse embryos share a common cell adhesion system with teratocarcinoma cells (1982) Dev. Biol., 92, pp. 521-528; Takeichi, M., The cadherins: cell-cell adhesion molecules controlling animal morphogenesis (1988) Development, 102, pp. 639-655; Fleming, T.P., Javed, Q., Hay, M., Epithelial differentiation and intercellular junction formation in the mouse early embryo (1992) Dev. Suppl., pp. 105-112; Aplin, J.D., Jones, C.J., Harris, L.K., Adhesion molecules in human trophoblast-a review. I. Villous trophoblast (2009) Placenta, 30, pp. 293-298; Nose, A., Takeichi, M., A novel cadherin cell adhesion molecule: its expression patterns associated with implantation and organogenesis of mouse embryos (1986) J. Cell Biol., 103, pp. 2649-2658; Larue, L., Ohsugi, M., Hirchenhain, J., Kemler, R., E-cadherin null mutant embryos fail to form a trophectoderm epithelium (1994) Proc. Natl. Acad. Sci. U. S. A., 91, pp. 8263-8267; Riethmacher, D., Brinkmann, V., Birchmeier, C., A targeted mutation in the mouse E-cadherin gene results in defective preimplantation development (1995) Proc. Natl. Acad. Sci. U. S. A., 92, pp. 855-859; Radice, G.L., Ferreira-Cornwell, M.C., Robinson, S.D., Rayburn, H., Chodosh, L.A., Takeichi, M., Hynes, R.O., Precocious mammary gland development in P-cadherin-deficient mice (1997) J. Cell Biol., 139, pp. 1025-1032; Frebourg, T., Oliveira, C., Hochain, P., Karam, R., Manouvrier, S., Graziadio, C., Vekemans, M., Seruca, R., Cleft lip/palate and CDH1/E-cadherin mutations in families with hereditary diffuse gastric cancer (2006) J. Med. Genet., 43, pp. 138-142; Kjaer, K.W., Hansen, L., Schwabe, G.C., Marques-de-Faria, A.P., Eiberg, H., Mundlos, S., Tommerup, N., Rosenberg, T., Distinct CDH3 mutations cause ectodermal dysplasia, ectrodactyly, macular dystrophy (EEM syndrome) (2005) J. Med. Genet., 42, pp. 292-298; Sprecher, E., Bergman, R., Richard, G., Lurie, R., Shalev, S., Petronius, D., Shalata, A., Szargel, R., Hypotrichosis with juvenile macular dystrophy is caused by a mutation in CDH3, encoding P-cadherin (2001) Nat. Genet., 29, pp. 134-136; Nelson, W.J., Epithelial cell polarity from the outside looking in (2003) News Physiol. Sci., 18, pp. 143-146; Hirai, Y., Nose, A., Kobayashi, S., Takeichi, M., Expression and role of E- and P-cadherin adhesion molecules in embryonic histogenesis. II. Skin morphogenesis (1989) Development, 105, pp. 271-277; Berx, G., Van Roy, F., The E-cadherin/catenin complex: an important gatekeeper in breast cancer tumorigenesis and malignant progression (2001) Breast Cancer Res., 3, pp. 289-293; Shimoyama, Y., Hirohashi, S., Expression of E- and P-cadherin in gastric carcinomas (1991) Cancer Res., 51, pp. 2185-2192; Hines, M.D., Jin, H.C., Wheelock, M.J., Jensen, P.J., Inhibition of cadherin function differentially affects markers of terminal differentiation in cultured human keratinocytes (1999) J. Cell Sci., 112 (PART 24), pp. 4569-4579; Ribeiro, A.S., Albergaria, A., Sousa, B., Correia, A.L., Bracke, M., Seruca, R., Schmitt, F.C., Paredes, J., Extracellular cleavage and shedding of P-cadherin: a mechanism underlying the invasive behaviour of breast cancer cells (2010) Oncogene, 29, pp. 392-402; Moll, R., Mitze, M., Frixen, U.H., Birchmeier, W., Differential loss of E-cadherin expression in infiltrating ductal and lobular breast carcinomas (1993) Am. J. Pathol., 143, pp. 1731-1742; Gamallo, C., Palacios, J., Suarez, A., Pizarro, A., Navarro, P., Quintanilla, M., Cano, A., Correlation of E-cadherin expression with differentiation grade and histological type in breast carcinoma (1993) Am. J. Pathol., 142, pp. 987-993; Reis-Filho, J.S., Cancela Paredes, J., Milanezi, F., Schmitt, F.C., Clinicopathologic implications of E-cadherin reactivity in patients with lobular carcinoma in situ of the breast (2002) Cancer, 94, pp. 2114-2115; author reply 2115-2116Weigelt, B., Geyer, F.C., Natrajan, R., Lopez-Garcia, M.A., Ahmad, A.S., Savage, K., Kreike, B., Reis-Filho, J.S., The molecular underpinning of lobular histological growth pattern: a genome-wide transcriptomic analysis of invasive lobular carcinomas and grade- and molecular subtype-matched invasive ductal carcinomas of no special type (2010) J. Pathol., 220, pp. 45-57; Simpson, P.T., Reis-Filho, J.S., Lambros, M.B., Jones, C., Steele, D., Mackay, A., Iravani, M., Lakhani, S.R., Molecular profiling pleomorphic lobular carcinomas of the breast: evidence for a common molecular genetic pathway with classic lobular carcinomas (2008) J. Pathol., 215, pp. 231-244; Mahler-Araujo, B., Savage, K., Parry, S., Reis-Filho, J.S., Reduction of E-cadherin expression is associated with non-lobular breast carcinomas of basal-like and triple negative phenotype (2008) J. Clin. Pathol., 61, pp. 615-620; Lopes, N., Carvalho, J., Duraes, C., Sousa, B., Gomes, M., Costa, J.L., Oliveira, C., Schmitt, F., 1Alpha,25-dihydroxyvitamin D3 induces de novo E-cadherin expression in triple-negative breast cancer cells by CDH1-promoter demethylation (2012) Anticancer. Res., 32, pp. 249-257; Berx, G., Cleton-Jansen, A.M., Strumane, K., de Leeuw, W.J., Nollet, F., van Roy, F., Cornelisse, C., E-cadherin is inactivated in a majority of invasive human lobular breast cancers by truncation mutations throughout its extracellular domain (1996) Oncogene, 13, pp. 1919-1925; Keller, G., Vogelsang, H., Becker, I., Hutter, J., Ott, K., Candidus, S., Grundei, T., Hofler, H., Diffuse type gastric and lobular breast carcinoma in a familial gastric cancer patient with an E-cadherin germline mutation (1999) Am. J. Pathol., 155, pp. 337-342; Schrader, K.A., Masciari, S., Boyd, N., Wiyrick, S., Kaurah, P., Senz, J., Burke, W., Huntsman, D.G., Hereditary diffuse gastric cancer: association with lobular breast cancer (2008) Fam. Cancer, 7, pp. 73-82; Becker, K.F., Atkinson, M.J., Reich, U., Becker, I., Nekarda, H., Siewert, J.R., Hofler, H., E-cadherin gene mutations provide clues to diffuse type gastric carcinomas (1994) Cancer Res., 54, pp. 3845-3852; Becker, K.F., Kremmer, E., Eulitz, M., Becker, I., Handschuh, G., Schuhmacher, C., Muller, W., Hofler, H., Analysis of E-cadherin in diffuse-type gastric cancer using a mutation-specific monoclonal antibody (1999) Am. J. Pathol., 155, pp. 1803-1809; Machado, J.C., Carneiro, F., Beck, S., Rossi, S., Lopes, J., Taveira-Gomes, A., Cardoso-Oliveira, M., E-cadherin expression is correlated with the isolated cell/diffuse histotype and with features of biological aggressiveness of gastric carcinoma (1998) Int. J. Surg. Pathol., 6, pp. 135-144; Carneiro, F., Machado, J.C., Seruca, R., Sobrinho-Simoes, M., E-cadherin changes in gastric carcimona (1999) Histopathology, 35, pp. 477-478; Carvalho, J., van Grieken, N.C., Pereira, P.M., Sousa, S., Tijssen, M., Buffart, T.E., Diosdado, B., Oliveira, C., Lack of microRNA-101 causes E-cadherin functional deregulation through EZH2 upregulation in intestinal gastric cancer (2012) J. Pathol.; Machado, J.C., Oliveira, C., Carvalho, R., Soares, P., Berx, G., Caldas, C., Seruca, R., Sobrinho-Simoes, M., E-cadherin gene (CDH1) promoter methylation as the second hit in sporadic diffuse gastric carcinoma (2001) Oncogene, 20, pp. 1525-1528; Guilford, P., Hopkins, J., Harraway, J., McLeod, M., McLeod, N., Harawira, P., Taite, H., Reeve, A.E., E-cadherin germline mutations in familial gastric cancer (1998) Nature, 392, pp. 402-405; Oliveira, C., Senz, J., Kaurah, P., Pinheiro, H., Sanges, R., Haegert, A., Corso, G., Huntsman, D., Germline CDH1 deletions in hereditary diffuse gastric cancer families (2009) Hum. Mol. Genet., 18, pp. 1545-1555; Pinheiro, H., Bordeira-Carrico, R., Seixas, S., Carvalho, J., Senz, J., Oliveira, P., Inacio, P., Oliveira, C., Allele-specific CDH1 downregulation and hereditary diffuse gastric cancer (2010) Hum. Mol. Genet., 19, pp. 943-952; Guilford, P., Humar, B., Blair, V., Hereditary diffuse gastric cancer: translation of CDH1 germline mutations into clinical practice (2010) Gastric Cancer, 13, pp. 1-10; Suriano, G., Seixas, S., Rocha, J., Seruca, R., A model to infer the pathogenic significance of CDH1 germline missense variants (2006) J. Mol. Med., 84, pp. 1023-1031; Suriano, G., Oliveira, C., Ferreira, P., Machado, J.C., Bordin, M.C., De Wever, O., Bruyneel, E.A., Seruca, R., Identification of CDH1 germline missense mutations associated with functional inactivation of the E-cadherin protein in young gastric cancer probands (2003) Hum. Mol. Genet., 12, pp. 575-582; Suriano, G., Oliveira, M.J., Huntsman, D., Mateus, A.R., Ferreira, P., Casares, F., Oliveira, C., Seruca, R., E-cadherin germline missense mutations and cell phenotype: evidence for the independence of cell invasion on the motile capabilities of the cells (2003) Hum. Mol. Genet., 12, pp. 3007-3016; Brooks-Wilson, A.R., Kaurah, P., Suriano, G., Leach, S., Senz, J., Grehan, N., Butterfield, Y.S., Huntsman, D., Germline E-cadherin mutations in hereditary diffuse gastric cancer: assessment of 42 new families and review of genetic screening criteria (2004) J. Med. Genet., 41, pp. 508-517; Kaurah, P., MacMillan, A., Boyd, N., Senz, J., De Luca, A., Chun, N., Suriano, G., Huntsman, D., Founder and recurrent CDH1 mutations in families with hereditary diffuse gastric cancer (2007) JAMA, 297, pp. 2360-2372; Corso, G., Roviello, F., Paredes, J., Pedrazzani, C., Novais, M., Correia, J., Marrelli, D., Suriano, G., Characterization of the P373L E-cadherin germline missense mutation and implication for clinical management (2007) Eur. J. Surg. Oncol., 33, pp. 1061-1067; More, H., Humar, B., Weber, W., Ward, R., Christian, A., Lintott, C., Graziano, F., Guilford, P., Identification of seven novel germline mutations in the human E-cadherin (CDH1) gene (2007) Hum. Mutat., 28, p. 203; Oliveira, C., de Bruin, J., Nabais, S., Ligtenberg, M., Moutinho, C., Nagengast, F.M., Seruca, R., Carneiro, F., Intragenic deletion of CDH1 as the inactivating mechanism of the wild-type allele in an HDGC tumour (2004) Oncogene, 23, pp. 2236-2240; Barber, M., Murrell, A., Ito, Y., Maia, A.T., Hyland, S., Oliveira, C., Save, V., Fitzgerald, R.C., Mechanisms and sequelae of E-cadherin silencing in hereditary diffuse gastric cancer (2008) J. Pathol., 216, pp. 295-306; Oliveira, C., Sousa, S., Pinheiro, H., Karam, R., Bordeira-Carrico, R., Senz, J., Kaurah, P., Seruca, R., Quantification of epigenetic and genetic 2nd hits in CDH1 during hereditary diffuse gastric cancer syndrome progression (2009) Gastroenterology, 136, pp. 2137-2148; Grady, W.M., Willis, J., Guilford, P.J., Dunbier, A.K., Toro, T.T., Lynch, H., Wiesner, G., Markowitz, S., Methylation of the CDH1 promoter as the second genetic hit in hereditary diffuse gastric cancer (2000) Nat. Genet., 26, pp. 16-17; Peinado, H., Ballestar, E., Esteller, M., Cano, A., Snail mediates E-cadherin repression by the recruitment of the Sin3A/histone deacetylase 1 (HDAC1)/HDAC2 complex (2004) Mol. Cell. Biol., 24, pp. 306-319; Fujii, S., Ochiai, A., Enhancer of zeste homolog 2 downregulates E-cadherin by mediating histone H3 methylation in gastric cancer cells (2008) Cancer Sci., 99, pp. 738-746; Cao, Q., Yu, J., Dhanasekaran, S.M., Kim, J.H., Mani, R.S., Tomlins, S.A., Mehra, R., Chinnaiyan, A.M., Repression of E-cadherin by the polycomb group protein EZH2 in cancer (2008) Oncogene, 27, pp. 7274-7284; Pena, C., Garcia, J.M., Silva, J., Garcia, V., Rodriguez, R., Alonso, I., Millan, I., Bonilla, F., E-cadherin and vitamin D receptor regulation by SNAIL and ZEB1 in colon cancer: clinicopathological correlations (2005) Hum. Mol. Genet., 14, pp. 3361-3370; Liu, Y., Hong, Y., Zhao, Y., Ismail, T.M., Wong, Y., Eu, K.W., Histone H3 (lys-9) deacetylation is associated with transcriptional silencing of E-cadherin in colorectal cancer cell lines (2008) Cancer Invest., 26, pp. 575-582; von Burstin, J., Eser, S., Paul, M.C., Seidler, B., Brandl, M., Messer, M., von Werder, A., Saur, D., E-cadherin regulates metastasis of pancreatic cancer in vivo and is suppressed by a SNAIL/HDAC1/HDAC2 repressor complex (2009) Gastroenterology, 137, pp. 361-371. , (371 e361-365); Herranz, N., Pasini, D., Diaz, V.M., Franci, C., Gutierrez, A., Dave, N., Escriva, M., Peiro, S., Polycomb complex 2 is required for E-cadherin repression by the Snail1 transcription factor (2008) Mol. Cell. Biol., 28, pp. 4772-4781; Ambros, V., The functions of animal microRNAs (2004) Nature, 431, pp. 350-355; He, L., Hannon, G.J., MicroRNAs: small RNAs with a big role in gene regulation (2004) Nat. Rev. Genet., 5, pp. 522-531; Hurteau, G.J., Carlson, J.A., Spivack, S.D., Brock, G.J., Overexpression of the microRNA hsa-miR-200c leads to reduced expression of transcription factor 8 and increased expression of E-cadherin (2007) Cancer Res., 67, pp. 7972-7976; Korpal, M., Lee, E.S., Hu, G., Kang, Y., The miR-200 family inhibits epithelial-mesenchymal transition and cancer cell migration by direct targeting of E-cadherin transcriptional repressors ZEB1 and ZEB2 (2008) J. Biol. Chem., 283, pp. 14910-14914; Gregory, P.A., Bert, A.G., Paterson, E.L., Barry, S.C., Tsykin, A., Farshid, G., Vadas, M.A., Goodall, G.J., The miR-200 family and miR-205 regulate epithelial to mesenchymal transition by targeting ZEB1 and SIP1 (2008) Nat. Cell Biol., 10, pp. 593-601; Park, S.M., Gaur, A.B., Lengyel, E., Peter, M.E., The miR-200 family determines the epithelial phenotype of cancer cells by targeting the E-cadherin repressors ZEB1 and ZEB2 (2008) Genes Dev., 22, pp. 894-907; Tan, H.X., Wang, Q., Chen, L.Z., Huang, X.H., Chen, J.S., Fu, X.H., Cao, L.Q., Zhang, L.J., MicroRNA-9 reduces cell invasion and E-cadherin secretion in SK-Hep-1 cell (2010) Med. Oncol., 27, pp. 654-660; Ma, L., Young, J., Prabhala, H., Pan, E., Mestdagh, P., Muth, D., Teruya-Feldstein, J., Weinberg, R.A., MiR-9, a MYC/MYCN-activated microRNA, regulates E-cadherin and cancer metastasis (2010) Nat. Cell Biol., 12, pp. 247-256; Oki, Y., Issa, J.P., Epigenetic mechanisms in AML-a target for therapy (2010) Cancer Treat. Res., 145, pp. 19-40; Simoes-Correia, J., Figueiredo, J., Oliveira, C., van Hengel, J., Seruca, R., van Roy, F., Suriano, G., Endoplasmic reticulum quality control: a new mechanism of E-cadherin regulation and its implication in cancer (2008) Hum. Mol. Genet., 17, pp. 3566-3576; Sitia, R., Braakman, I., Quality control in the endoplasmic reticulum protein factory (2003) Nature, 426, pp. 891-894; Meusser, B., Hirsch, C., Jarosch, E., Sommer, T., ERAD: the long road to destruction (2005) Nat. Cell Biol., 7, pp. 766-772; van Hengel, J., van Roy, F., Diverse functions of p120ctn in tumors (2007) Biochim. Biophys. Acta, 1773, pp. 78-88; Jawhari, A.U., Noda, M., Pignatelli, M., Farthing, M., Up-regulated cytoplasmic expression, with reduced membranous distribution, of the src substrate p120(ctn) in gastric carcinoma (1999) J. Pathol., 189, pp. 180-185; Karayiannakis, A.J., Syrigos, K.N., Alexiou, D., Kalahanis, N., Rosenberg, T., Bastounis, E., Pignatelli, M., Expression patterns of the novel catenin p120cas in gastrointestinal cancers (1999) Anticancer. Res., 19, pp. 4401-4405; Karatzas, G., Karayiannakis, A.J., Syrigos, K.N., Chatzigianni, E., Papanikolaou, S., Simatos, G., Papanikolaou, D., Bogris, S., Expression patterns of the E-cadherin-catenin cell-cell adhesion complex in gastric cancer (2000) Hepatogastroenterology, 47, pp. 1465-1469; Apweiler, R., Hermjakob, H., Sharon, N., On the frequency of protein glycosylation, as deduced from analysis of the SWISS-PROT database (1999) Biochim. Biophys. Acta, 1473, pp. 4-8; Dube, D.H., Bertozzi, C.R., Glycans in cancer and inflammation-potential for therapeutics and diagnostics (2005) Nat. Rev. Drug Discov., 4, pp. 477-488; Pinho, S.S., Osorio, H., Nita-Lazar, M., Gomes, J., Lopes, C., Gartner, F., Reis, C.A., Role of E-cadherin N-glycosylation profile in a mammary tumor model (2009) Biochem. Biophys. Res. Commun., 379, pp. 1091-1096; Iijima, J., Zhao, Y., Isaji, T., Kameyama, A., Nakaya, S., Wang, X., Ihara, H., Gu, J., Cell-cell interaction-dependent regulation of N-acetylglucosaminyltransferase III and the bisected N-glycans in GE11 epithelial cells. Involvement of E-cadherin-mediated cell adhesion (2006) J. Biol. Chem., 281, pp. 13038-13046; Yoshimura, M., Ihara, Y., Matsuzawa, Y., Taniguchi, N., Aberrant glycosylation of E-cadherin enhances cell-cell binding to suppress metastasis (1996) J. Biol. Chem., 271, pp. 13811-13815; Giles, R.H., van Es, J.H., Clevers, H., Caught up in a Wnt storm: Wnt signaling in cancer (2003) Biochim. Biophys. Acta, 1653, pp. 1-24; Reynolds, A.B., Roczniak-Ferguson, A., Emerging roles for p120-catenin in cell adhesion and cancer (2004) Oncogene, 23, pp. 7947-7956; Christofori, G., Changing neighbours, changing behaviour: cell adhesion molecule-mediated signalling during tumour progression (2003) EMBO J., 22, pp. 2318-2323; Gottardi, C.J., Wong, E., Gumbiner, B.M., E-cadherin suppresses cellular transformation by inhibiting beta-catenin signaling in an adhesion-independent manner (2001) J. Cell Biol., 153, pp. 1049-1060; Stockinger, A., Eger, A., Wolf, J., Beug, H., Foisner, R., E-cadherin regulates cell growth by modulating proliferation-dependent beta-catenin transcriptional activity (2001) J. Cell Biol., 154, pp. 1185-1196; Suriano, G., Mulholland, D., de Wever, O., Ferreira, P., Mateus, A.R., Bruyneel, E., Nelson, C.C., Seruca, R., The intracellular E-cadherin germline mutation V832 M lacks the ability to mediate cell-cell adhesion and to suppress invasion (2003) Oncogene, 22, pp. 5716-5719; Sahai, E., Marshall, C.J., RHO-GTPases and cancer (2002) Nat. Rev. Cancer, 2, pp. 133-142; Deplazes, J., Fuchs, M., Rauser, S., Genth, H., Lengyel, E., Busch, R., Luber, B., Rac1 and Rho contribute to the migratory and invasive phenotype associated with somatic E-cadherin mutation (2009) Hum. Mol. Genet., 18, pp. 3632-3644; Mateus, A.R., Seruca, R., Machado, J.C., Keller, G., Oliveira, M.J., Suriano, G., Luber, B., EGFR regulates RhoA-GTP dependent cell motility in E-cadherin mutant cells (2007) Hum. Mol. Genet., 16, pp. 1639-1647; Mateus, A.R., Simoes-Correia, J., Figueiredo, J., Heindl, S., Alves, C.C., Suriano, G., Luber, B., Seruca, R., E-cadherin mutations and cell motility: a genotype-phenotype correlation (2009) Exp. Cell Res., 315, pp. 1393-1402; Crepaldi, T., Pollack, A.L., Prat, M., Zborek, A., Mostov, K., Comoglio, P.M., Targeting of the SF/HGF receptor to the basolateral domain of polarized epithelial cells (1994) J. Cell Biol., 125, pp. 313-320; Pece, S., Gutkind, J.S., Signaling from E-cadherins to the MAPK pathway by the recruitment and activation of epidermal growth factor receptors upon cell-cell contact formation (2000) J. Biol. Chem., 275, pp. 41227-41233; Thiery, J.P., Epithelial-mesenchymal transitions in tumour progression (2002) Nat. Rev. Cancer, 2, pp. 442-454; Qian, X., Karpova, T., Sheppard, A.M., McNally, J., Lowy, D.R., E-cadherin-mediated adhesion inhibits ligand-dependent activation of diverse receptor tyrosine kinases (2004) EMBO J., 23, pp. 1739-1748; Takahashi, K., Suzuki, K., Density-dependent inhibition of growth involves prevention of EGF receptor activation by E-cadherin-mediated cell-cell adhesion (1996) Exp. Cell Res., 226, pp. 214-222; Mook, O.R., Frederiks, W.M., Van Noorden, C.J., The role of gelatinases in colorectal cancer progression and metastasis (2004) Biochim. Biophys. Acta, 1705, pp. 69-89; Munshi, H.G., Ghosh, S., Mukhopadhyay, S., Wu, Y.I., Sen, R., Green, K.J., Stack, M.S., Proteinase suppression by E-cadherin-mediated cell-cell attachment in premalignant oral keratinocytes (2002) J. Biol. Chem., 277, pp. 38159-38167; Lochter, A., Galosy, S., Muschler, J., Freedman, N., Werb, Z., Bissell, M.J., Matrix metalloproteinase stromelysin-1 triggers a cascade of molecular alterations that leads to stable epithelial-to-mesenchymal conversion and a premalignant phenotype in mammary epithelial cells (1997) J. Cell Biol., 139, pp. 1861-1872; Davies, G., Jiang, W.G., Mason, M.D., Matrilysin mediates extracellular cleavage of E-cadherin from prostate cancer cells: a key mechanism in hepatocyte growth factor/scatter factor-induced cell-cell dissociation and in vitro invasion (2001) Clin. Cancer Res., 7, pp. 3289-3297; Noe, V., Fingleton, B., Jacobs, K., Crawford, H.C., Vermeulen, S., Steelant, W., Bruyneel, E., Mareel, M., Release of an invasion promoter E-cadherin fragment by matrilysin and stromelysin-1 (2001) J. Cell Sci., 114, pp. 111-118; Ryniers, F., Stove, C., Goethals, M., Brackenier, L., Noe, V., Bracke, M., Vandekerckhove, J., Bruyneel, E., Plasmin produces an E-cadherin fragment that stimulates cancer cell invasion (2002) Biol. Chem., 383, pp. 159-165; Comoglio, P.M., Boccaccio, C., Trusolino, L., Interactions between growth factor receptors and adhesion molecules: breaking the rules (2003) Curr. Opin. Cell Biol., 15, pp. 565-571; Ferreira, P., Oliveira, M.J., Beraldi, E., Mateus, A.R., Nakajima, T., Gleave, M., Yokota, J., Suriano, G., Loss of functional E-cadherin renders cells more resistant to the apoptotic agent taxol in vitro (2005) Exp. Cell Res., 310, pp. 99-104; Ferreira, A.C., Suriano, G., Mendes, N., Gomes, B., Wen, X., Carneiro, F., Seruca, R., Machado, J.C., E-cadherin impairment increases cell survival through Notch-dependent upregulation of Bcl-2 (2012) Hum. Mol. Genet., 21, pp. 334-343; Huang, F.Y., Chan, A.O., Rashid, A., Wong, D.K., Cho, C.H., Yuen, M.F., Helicobacter pylori induces promoter methylation of E-cadherin via interleukin-1beta activation of nitric oxide production in gastric cancer cells (2012) Cancer; Chan, A.O., Lam, S.K., Wong, B.C., Wong, W.M., Yuen, M.F., Yeung, Y.H., Hui, W.M., Kwong, Y.L., Promoter methylation of E-cadherin gene in gastric mucosa associated with Helicobacter pylori infection and in gastric cancer (2003) Gut, 52, pp. 502-506; Leung, W.K., Man, E.P., Yu, J., Go, M.Y., To, K.F., Yamaoka, Y., Cheng, V.Y., Sung, J.J., Effects of Helicobacter pylori eradication on methylation status of E-cadherin gene in noncancerous stomach (2006) Clin. Cancer Res., 12, pp. 3216-3221; Perri, F., Cotugno, R., Piepoli, A., Merla, A., Quitadamo, M., Gentile, A., Pilotto, A., Andriulli, A., Aberrant DNA methylation in non-neoplastic gastric mucosa of H. pylori infected patients and effect of eradication (2007) Am. J. Gastroenterol., 102, pp. 1361-1371; Chan, A.O., Peng, J.Z., Lam, S.K., Lai, K.C., Yuen, M.F., Cheung, H.K., Kwong, Y.L., Wong, B.C., Eradication of Helicobacter pylori infection reverses E-cadherin promoter hypermethylation (2006) Gut, 55, pp. 463-468; Schirrmeister, W., Gnad, T., Wex, T., Higashiyama, S., Wolke, C., Naumann, M., Lendeckel, U., Ectodomain shedding of E-cadherin and c-Met is induced by Helicobacter pylori infection (2009) Exp. Cell Res., 315, pp. 3500-3508; Hoy, B., Lower, M., Weydig, C., Carra, G., Tegtmeyer, N., Geppert, T., Schroder, P., Wessler, S., Helicobacter pylori HtrA is a new secreted virulence factor that cleaves E-cadherin to disrupt intercellular adhesion (2010) EMBO Rep., 11, pp. 798-804; O'Connor, P.M., Lapointe, T.K., Jackson, S., Beck, P.L., Jones, N.L., Buret, A.G., Helicobacter pylori activates calpain via toll-like receptor 2 to disrupt adherens junctions in human gastric epithelial cells (2011) Infect. Immun., 79, pp. 3887-3894; Conlin, V.S., Curtis, S.B., Zhao, Y., Moore, E.D., Smith, V.C., Meloche, R.M., Finlay, B.B., Buchan, A.M., Helicobacter pylori infection targets adherens junction regulatory proteins and results in increased rates of migration in human gastric epithelial cells (2004) Infect. Immun., 72, pp. 5181-5192; Suzuki, M., Mimuro, H., Suzuki, T., Park, M., Yamamoto, T., Sasakawa, C., Interaction of CagA with Crk plays an important role in Helicobacter pylori-induced loss of gastric epithelial cell adhesion (2005) J. Exp. Med., 202, pp. 1235-1247; Franco, A.T., Israel, D.A., Washington, M.K., Krishna, U., Fox, J.G., Rogers, A.B., Neish, A.S., Peek, R.M., Activation of beta-catenin by carcinogenic Helicobacter pylori (2005) Proc. Natl. Acad. Sci. U. S. A., 102, pp. 10646-10651; Murata-Kamiya, N., Kurashima, Y., Teishikata, Y., Yamahashi, Y., Saito, Y., Higashi, H., Aburatani, H., Hatakeyama, M., Helicobacter pylori CagA interacts with E-cadherin and deregulates the beta-catenin signal that promotes intestinal transdifferentiation in gastric epithelial cells (2007) Oncogene, 26, pp. 4617-4626; Sokolova, O., Bozko, P.M., Naumann, M., Helicobacter pylori suppresses glycogen synthase kinase 3beta to promote beta-catenin activity (2008) J. Biol. Chem., 283, pp. 29367-29374; Ogden, S.R., Wroblewski, L.E., Weydig, C., Romero-Gallo, J., O'Brien, D.P., Israel, D.A., Krishna, U.S., Peek, R.M., P120 and Kaiso regulate Helicobacter pylori-induced expression of matrix metalloproteinase-7 (2008) Mol. Biol. Cell, 19, pp. 4110-4121; Bebb, J.R., Leach, L., Zaitoun, A., Hand, N., Letley, D.P., Thomas, R., Atherton, J.C., Effects of Helicobacter pylori on the cadherin-catenin complex (2006) J. Clin. Pathol., 59, pp. 1261-1266; Oliveira, M.J., Costa, A.M., Costa, A.C., Ferreira, R.M., Sampaio, P., Machado, J.C., Seruca, R., Figueiredo, C., CagA associates with c-Met, E-cadherin, and p120-catenin in a multiproteic complex that suppresses Helicobacter pylori-induced cell-invasive phenotype (2009) J. Infect. Dis., 200, pp. 745-755; Oliveira, M.J., Costa, A.C., Costa, A.M., Henriques, L., Suriano, G., Atherton, J.C., Machado, J.C., Figueiredo, C., Helicobacter pylori induces gastric epithelial cell invasion in a c-Met and type IV secretion system-dependent manner (2006) J. Biol. Chem., 281, pp. 34888-34896; Jang, A.C., Starz-Gaiano, M., Montell, D.J., Modeling migration and metastasis in Drosophila (2007) J. Mammary Gland Biol. Neoplasia, 12, pp. 103-114; Pereira, P.S., Teixeira, A., Pinho, S., Ferreira, P., Fernandes, J., Oliveira, C., Seruca, R., Casares, F., E-cadherin missense mutations, associated with hereditary diffuse gastric cancer (HDGC) syndrome, display distinct invasive behaviors and genetic interactions with the Wnt and Notch pathways in Drosophila epithelia (2006) Hum. Mol. Genet., 15, pp. 1704-1712; Caldeira, J., Pereira, P.S., Suriano, G., Casares, F., Using fruitflies to help understand the molecular mechanisms of human hereditary diffuse gastric cancer (2009) Int. J. Dev. Biol., 53, pp. 1557-1561; Humar, B., Blair, V., Charlton, A., More, H., Martin, I., Guilford, P., E-cadherin deficiency initiates gastric signet-ring cell carcinoma in mice and man (2009) Cancer Res., 69, pp. 2050-2056; Mbalaviele, G., Dunstan, C.R., Sasaki, A., Williams, P.J., Mundy, G.R., Yoneda, T., E-cadherin expression in human breast cancer cells suppresses the development of osteolytic bone metastases in an experimental metastasis model (1996) Cancer Res., 56, pp. 4063-4070; Perl, A.K., Wilgenbus, P., Dahl, U., Semb, H., Christofori, G., A causal role for E-cadherin in the transition from adenoma to carcinoma (1998) Nature, 392, pp. 190-193; Kuwabara, Y., Yamada, T., Yamazaki, K., Du, W.L., Banno, K., Aoki, D., Sakamoto, M., Establishment of an ovarian metastasis model and possible involvement of E-cadherin down-regulation in the metastasis (2008) Cancer Sci., 99, pp. 1933-1939; Shimoyama, Y., Hirohashi, S., Hirano, S., Noguchi, M., Shimosato, Y., Takeichi, M., Abe, O., Cadherin cell-adhesion molecules in human epithelial tissues and carcinomas (1989) Cancer Res., 49, pp. 2128-2133; Sanders, D.S., Bruton, R., Darnton, S.J., Casson, A.G., Hanson, I., Williams, H.K., Jankowski, J., Sequential changes in cadherin-catenin expression associated with the progression and heterogeneity of primary oesophageal squamous carcinoma (1998) Int. J. Cancer, 79, pp. 573-579; Rocha, A.S., Soares, P., Machado, J.C., Maximo, V., Fonseca, E., Franssila, K., Sobrinho-Simoes, M., Mucoepidermoid carcinoma of the thyroid: a tumour histotype characterised by P-cadherin neoexpression and marked abnormalities of E-cadherin/catenins complex (2002) Virchows Arch., 440, pp. 498-504; Kim, M.A., Jung, E.J., Lee, H.S., Lee, H.E., Yang, H.K., Oh, D.Y., Bang, Y.J., Kim, W.H., P-cadherin expression in gastric carcinoma: its regulation mechanism and prognostic significance (2010) Hum. Pathol., 41, pp. 877-885; Imai, K., Hirata, S., Irie, A., Senju, S., Ikuta, Y., Yokomine, K., Harao, M., Nishimura, Y., Identification of a novel tumor-associated antigen, cadherin 3/P-cadherin, as a possible target for immunotherapy of pancreatic, gastric, and colorectal cancers (2008) Clin. Cancer Res., 14, pp. 6487-6495; Lo Muzio, L., Campisi, G., Farina, A., Rubini, C., Pannone, G., Serpico, R., Laino, G., Carinci, F., P-cadherin expression and survival rate in oral squamous cell carcinoma: an immunohistochemical study (2005) BMC Cancer, 5, p. 63; Han, A.C., Edelson, M.I., Peralta Soler, A., Knudsen, K.A., Lifschitz-Mercer, B., Czernobilsky, B., Rosenblum, N.G., Salazar, H., Cadherin expression in glandular tumors of the cervix (2000) Cancer, 89, pp. 2053-2058; Longatto Filho, A., Albergaria, A., Paredes, J., Moreira, M.A., Milanezi, F., Schmitt, F.C., P-cadherin expression in glandular lesions of the uterine cervix detected by liquid-based cytology (2005) Cytopathology, 16, pp. 88-93; Stefansson, I.M., Salvesen, H.B., Akslen, L.A., Prognostic impact of alterations in P-cadherin expression and related cell adhesion markers in endometrial cancer (2004) J. Clin. Oncol., 22, pp. 1242-1252; Moreno-Bueno, G., Hardisson, D., Sarrio, D., Sanchez, C., Cassia, R., Prat, J., Herman, J.G., Palacios, J., Abnormalities of E- and P-cadherin and catenin (beta-, gamma-catenin, and p120ctn) expression in endometrial cancer and endometrial atypical hyperplasia (2003) J. Pathol., 199, pp. 471-478; Quattrocchi, L., Green, A.R., Martin, S., Durrant, L., Deen, S., The cadherin switch in ovarian high-grade serous carcinoma is associated with disease progression (2011) Virchows Arch., 459, pp. 21-29; Sarrio, D., Moreno-Bueno, G., Sanchez-Estevez, C., Banon-Rodriguez, I., Hernandez-Cortes, G., Hardisson, D., Palacios, J., Expression of cadherins and catenins correlates with distinct histologic types of ovarian carcinomas (2006) Hum. Pathol., 37, pp. 1042-1049; Soler, A.P., Harner, G.D., Knudsen, K.A., McBrearty, F.X., Grujic, E., Salazar, H., Han, A.C., Keshgegian, A.A., Expression of P-cadherin identifies prostate-specific-antigen-negative cells in epithelial tissues of male sexual accessory organs and in prostatic carcinomas. Implications for prostate cancer biology (1997) Am. J. Pathol., 151, pp. 471-478; Bryan, R.T., Atherfold, P.A., Yeo, Y., Jones, L.J., Harrison, R.F., Wallace, D.M., Jankowski, J.A., Cadherin switching dictates the biology of transitional cell carcinoma of the bladder: ex vivo and in vitro studies (2008) J. Pathol., 215, pp. 184-194; Matos, I., Dufloth, R., Alvarenga, M., Zeferino, L.C., Schmitt, F., P63, cytokeratin 5, and P-cadherin: three molecular markers to distinguish basal phenotype in breast carcinomas (2005) Virchows Arch., 447, pp. 688-694; Arnes, J.B., Brunet, J.S., Stefansson, I., Begin, L.R., Wong, N., Chappuis, P.O., Akslen, L.A., Foulkes, W.D., Placental cadherin and the basal epithelial phenotype of BRCA1-related breast cancer (2005) Clin. Cancer Res., 11, pp. 4003-4011; Palacios, J., Benito, N., Pizarro, A., Suarez, A., Espada, J., Cano, A., Gamallo, C., Anomalous expression of P-cadherin in breast carcinoma. Correlation with E-cadherin expression and pathological features (1995) Am. J. Pathol., 146, pp. 605-612; Peralta Soler, A., Knudsen, K.A., Salazar, H., Han, A.C., Keshgegian, A.A., P-cadherin expression in breast carcinoma indicates poor survival (1999) Cancer, 86, pp. 1263-1272; Paredes, J., Milanezi, F., Reis-Filho, J.S., Leitao, D., Athanazio, D., Schmitt, F., Aberrant P-cadherin expression: is it associated with estrogen-independent growth in breast cancer? (2002) Pathol. Res. Pract., 198, pp. 795-801; Kovacs, A., Dhillon, J., Walker, R.A., Expression of P-cadherin, but not E-cadherin or N-cadherin, relates to pathological and functional differentiation of breast carcinomas (2003) Mol. Pathol., 56, pp. 318-322; Gamallo, C., Moreno-Bueno, G., Sarrio, D., Calero, F., Hardisson, D., Palacios, J., The prognostic significance of P-cadherin in infiltrating ductal breast carcinoma (2001) Mod. Pathol., 14, pp. 650-654; Paredes, J., Correia, A.L., Ribeiro, A.S., Milanezi, F., Cameselle-Teijeiro, J., Schmitt, F.C., Breast carcinomas that co-express E- and P-cadherin are associated with p120-catenin cytoplasmic localisation and poor patient survival (2008) J. Clin. Pathol., 61, pp. 856-862; Foulkes, W.D., Stefansson, I.M., Chappuis, P.O., Begin, L.R., Goffin, J.R., Wong, N., Trudel, M., Akslen, L.A., Germline BRCA1 mutations and a basal epithelial phenotype in breast cancer (2003) J. Natl. Cancer Inst., 95, pp. 1482-1485; Lakhani, S.R., Reis-Filho, J.S., Fulford, L., Penault-Llorca, F., van der Vijver, M., Parry, S., Bishop, T., Easton, D.F., Prediction of BRCA1 status in patients with breast cancer using estrogen receptor and basal phenotype (2005) Clin. Cancer Res., 11, pp. 5175-5180; Palacios, J., Honrado, E., Osorio, A., Cazorla, A., Sarrio, D., Barroso, A., Rodriguez, S., Benitez, J., Immunohistochemical characteristics defined by tissue microarray of hereditary breast cancer not attributable to BRCA1 or BRCA2 mutations: differences from breast carcinomas arising in BRCA1 and BRCA2 mutation carriers (2003) Clin. Cancer Res., 9, pp. 3606-3614; Palacios, J., Honrado, E., Osorio, A., Cazorla, A., Sarrio, D., Barroso, A., Rodriguez, S., Benitez, J., Phenotypic characterization of BRCA1 and BRCA2 tumors based in a tissue microarray study with 37 immunohistochemical markers (2005) Breast Cancer Res. Treat., 90, pp. 5-14; Gorski, J.J., James, C.R., Quinn, J.E., Stewart, G.E., Staunton, K.C., Buckley, N.E., McDyer, F.A., Harkin, D.P., BRCA1 transcriptionally regulates genes associated with the basal-like phenotype in breast cancer (2010) Breast Cancer Res. Treat., 122, pp. 721-731; Albergaria, A., Ribeiro, A.S., Pinho, S., Milanezi, F., Carneiro, V., Sousa, B., Sousa, S., Schmitt, F., ICI 182,780 induces P-cadherin overexpression in breast cancer cells through chromatin remodelling at the promoter level: a role for C/EBPbeta in CDH3 gene activation (2010) Hum. Mol. Genet., 19, pp. 2554-2566; Sato, N., Fukushima, N., Maitra, A., Matsubayashi, H., Yeo, C.J., Cameron, J.L., Hruban, R.H., Goggins, M., Discovery of novel targets for aberrant methylation in pancreatic carcinoma using high-throughput microarrays (2003) Cancer Res., 63, pp. 3735-3742; Milicic, A., Harrison, L.A., Goodlad, R.A., Hardy, R.G., Nicholson, A.M., Presz, M., Sieber, O., Jankowski, J.A., Ectopic expression of P-cadherin correlates with promoter hypomethylation early in colorectal carcinogenesis and enhanced intestinal crypt fission in vivo (2008) Cancer Res., 68, pp. 7760-7768; Van Marck, V., Stove, C., Van Den Bossche, K., Stove, V., Paredes, J., Vander Haeghen, Y., Bracke, M., P-cadherin promotes cell-cell adhesion and counteracts invasion in human melanoma (2005) Cancer Res., 65, pp. 8774-8783; Sarrio, D., Palacios, J., Hergueta-Redondo, M., Gomez-Lopez, G., Cano, A., Moreno-Bueno, G., Functional characterization of E- and P-cadherin in invasive breast cancer cells (2009) BMC Cancer, 9, p. 74; Bauer, K., Dowejko, A., Bosserhoff, A.K., Reichert, T.E., Bauer, R.J., P-cadherin induces an epithelial-like phenotype in oral squamous cell carcinoma by GSK-3beta-mediated Snail phosphorylation (2009) Carcinogenesis, 30, pp. 1781-1788; Bauer, K., Dowejko, A., Bosserhoff, A.K., Reichert, T.E., Bauer, R., Slit-2 facilitates interaction of P-cadherin with Robo-3 and inhibits cell migration in an oral squamous cell carcinoma cell line (2011) Carcinogenesis, 32, pp. 935-943; Mandeville, J.A., Silva Neto, B., Vanni, A.J., Smith, G.L., Rieger-Christ, K.M., Zeheb, R., Loda, M., Summerhayes, I.C., P-cadherin as a prognostic indicator and a modulator of migratory behaviour in bladder carcinoma cells (2008) BJU Int., 102, pp. 1707-1714; Cheung, L.W., Leung, P.C., Wong, A.S., Cadherin switching and activation of p120 catenin signaling are mediators of gonadotropin-releasing hormone to promote tumor cell migration and invasion in ovarian cancer (2010) Oncogene, 29, pp. 2427-2440; Reynolds, A.B., Daniel, J.M., Mo, Y.Y., Wu, J., Zhang, Z., The novel catenin p120cas binds classical cadherins and induces an unusual morphological phenotype in NIH3T3 fibroblasts (1996) Exp. Cell Res., 225, pp. 328-337; Baki, L., Marambaud, P., Efthimiopoulos, S., Georgakopoulos, A., Wen, P., Cui, W., Shioi, J., Robakis, N.K., Presenilin-1 binds cytoplasmic epithelial cadherin, inhibits cadherin/p120 association, and regulates stability and function of the cadherin/catenin adhesion complex (2001) Proc. Natl. Acad. Sci. U. S. A., 98, pp. 2381-2386; Jacobs, K., Van Gele, M., Forsyth, R., Brochez, L., Vanhoecke, B., De Wever, O., Bracke, M., P-cadherin counteracts myosin II-B function: implications in melanoma progression (2010) Mol. Cancer, 9, p. 255; Radice, G.L., Sauer, C.L., Kostetskii, I., Peralta Soler, A., Knudsen, K.A., Inappropriate P-cadherin expression in the mouse mammary epithelium is compatible with normal mammary gland function (2003) Differentiation, 71, pp. 361-373; Gregory, D.J., Mikhaylova, L., Fedulov, A.V., Selective DNA demethylation by fusion of TDG with a sequence-specific DNA-binding domain (2012) Epigenetics, 7; Zhang, C.C., Yan, Z., Zhang, Q., Kuszpit, K., Zasadny, K., Qiu, M., Painter, C.L., VanArsdale, T., PF-03732010: a fully human monoclonal antibody against P-cadherin with antitumor and antimetastatic activity (2010) Clin. Cancer Res., 16, pp. 5177-5188
Keywords: antineoplastic activity; antineoplastic agent; Breast; breast cancer; Cancer; cancer chemotherapy; cancer model; cancer survival; drug effect; E-cadherin; Gastric; gene expression regulation; gene function; gene location; gene overexpression; gene structure; genetic association; genetic code; Helicobacter infection; Hereditary diffuse gastric cancer; human; in vivo study; loss of function mutation; lymph node metastasis; malignant neoplastic disease; molecular dynamics; molecular pathology; molecularly targeted therapy; nonhuman; P cadherin; P cadherin gene; P-cadherin; pf 03732010; priority journal; protein expression; protein function; protein inhibitor; protein processing; review; signal transduction; stomach cancer; transcription regulation; tumor gene; unclassified drug; uvomorulin; uvomorulin gene; vasculotropin inhibitor

The importance of antimicrobial peptides and their potential for therapeutic use in ophthalmology - Silva, N.C.; Sarmento, B.; Pintado, M. (International Journal of Antimicrobial AgentsInt. J. Antimicrob. Agents, 2012)
The reduced effectiveness of some of the most important antibiotics owing to increasing resistance of microorganisms as well as the absence of new classes of antimicrobial agents have been concerning researchers and clinicians in recent years. Thus, the development and approval of new compounds for clinical applications is of great importance. Among these compounds, antimicrobial peptides (AMPs) appear to be excellent candidates for the development of novel antimicrobial agents. Some AMPs and antimicrobial proteins have been shown to be active against relevant pathogens in ocular infections as well as in biofilm eradication from contact lenses. Thus, they are considered promising in the prevention and management of ocular diseases. This review summarises the main classes and characteristics of AMPs and antimicrobial proteins, in particular those found in ocular structures and fluids. Some AMPs with activity against ocular pathogens and their potential as therapeutic agents to treat and prevent ocular infections are emphasised. © 2012.
Keywords: Antimicrobial peptide; Antimicrobial protein; Ocular infection; Ophthalmology

Interactions of microbicide nanoparticles with a simulated vaginal fluid - Das Neves, J.; Rocha, C.M.R.; Gonçalves, M.P.; Carrier, R.L.; Amiji, M.; Bahia, M.F.; Sarmento, B. (Molecular PharmaceuticsMol. Pharm., 2012)
The interaction with cervicovaginal mucus presents the potential to impact the performance of drug nanocarriers. These systems must migrate through this biological fluid in order to deliver their drug payload to the underlying mucosal surface. We studied the ability of dapivirine-loaded polycaprolactone (PCL)-based nanoparticles (NPs) to interact with a simulated vaginal fluid (SVF) incorporating mucin. Different surface modifiers were used to produce NPs with either negative (poloxamer 338 NF and sodium lauryl sulfate) or positive (cetyltrimethylammonium bromide) surface charge. Studies were performed using the mucin particle method, rheological measurements, and real-time multiple particle tracking. Results showed that SVF presented rheological properties similar to those of human cervicovaginal mucus. Analysis of NP transport indicated mild interactions with mucin and low adhesive potential. In general, negatively charged NPs underwent subdiffusive transport in SVF, i.e., hindered as compared to their diffusion in water, but faster than for positively charged NPs. These differences were increased when the pH of SVF was changed from 4.2 to 7.0. Diffusivity was 50- and 172-fold lower in SVF at pH 4.2 than in water for negatively charged and positively charged NPs, respectively. At pH 7.0, this decrease was around 20- and 385-fold, respectively. The estimated times required to cross a layer of SVF were equal to or lower than 1.7 h for negatively charged NPs, while for positively charged NPs these values were equal to or higher than 7 h. Overall, our results suggest that negatively charged PCL NPs may be suitable to be used as carriers in order to deliver dapivirine and potentially other antiretroviral drugs to the cervicovaginal mucosal lining. Also, they further reinforce the importance in characterizing the interactions of nanosystems with mucus fluids or surrogates when considering mucosal drug delivery. © 2012 American Chemical Society.
Keywords: microbicides; mucin; mucoadhesion; mucosal drug delivery; particle tracking; rheology

Methamphetamine mimics the neurochemical profile of aging in rats and impairs recognition memory - Melo, P.; Magalhães, A.; Alves, C.J.; Tavares, M.A.; De Sousa, L.; Summavielle, T.; Moradas-Ferreira, P. (NeuroToxicologyNeuroToxicology, 2012)
Brain neurochemistry and cognition performance are thought to decline with age. Accumulating data indicate that similar events occur after prolonged methamphetamine (MA) exposure. Using the rat as a model, the present study was designed to uncover common alteration patterns in brain neurochemistry and memory performance between aging and prolonged MA exposure. To this end, animals were treated with a chronic binge MA administration paradigm (20. mg/kg/day from postnatal day 91 to 100). Three-age control groups received isovolumetric saline treatment and were tested at the MA age-matched period, and at 12 and 20 months. We observed that both MA and aged animals presented a long, but not short, time impairment in novelty preference and an increased anxiety-like behavior. Neurochemical analysis indicated similar MA- and age-related impairments in dopamine, serotonin and metabolites in the striatum, prefrontal cortex and hippocampus. Thus, the present data illustrate that MA may be used to mimic age-related effects on neurotransmitter systems and advocate MA treatment as a feasible animal model to study neuronal processes associated with aging. © 2012 Elsevier Inc.
Keywords: Accelerated aging; Age Factors; aging; animal behavior; animal experiment; animal model; animal tissue; Animalia; Animals; anxiety; article; behavior change; Behavior, Animal; Brain; Brain Chemistry; controlled study; corpus striatum; dopamine; Exploratory Behavior; hippocampus; Hydroxyindoleacetic Acid; long term exposure; male; Memory Disorders; mental performance; Methamphetamine; Neurochemistry; neurotransmission; nonhuman; perinatal drug exposure; prefrontal cortex; priority journal; rat; Rats; Rats, Wistar; Rattus; recognition; Recognition (Psychology); Recognition memory; serotonin; sodium chloride; Time Factors

Neuropeptide Y Y1 receptor antagonism increases bone mass in mice - Sousa, D.M.; Baldock, P.A.; Enriquez, R.F.; Zhang, L.; Sainsbury, A.; Lamghari, M.; Herzog, H. (BoneBone, 2012)
The neuropeptide Y system has emerged as one of the major neural signalling pathways regulating bone homeostasis. Absence of Y1 receptor signalling from bone forming osteoblasts is responsible for an enhancement on bone mass in mice, suggesting that pharmacological blockade of Y1 receptors may offer a novel anabolic treatment option for improving bone mass. Here we show that oral administration of the selective Y1 receptor antagonist BIBO3304 for 8. weeks dose-dependently increases bone mass in mice. Histomorphometric analysis revealed a significant 1.5-fold increase in cancellous bone volume in the femora of mice treated with BIBO3304. Furthermore, bone microarchitecture was improved, with greater trabecular number and trabecular thickness. This increase in bone mass was associated with a significant increase in bone anabolic activity of osteoblasts and, interestingly, was evident despite a coincident increase in bone resorption, as evidenced by an increase in the number of the osteolytic osteoclasts. Changes were also evident in cortical bone, with a significant increase in periosteal mineral apposition rate. Importantly, no adverse extra-skeletal side effects were observed through Y1 receptor antagonism over the 8-week treatment period, with no effects of even the higher BIBO3304 dose on body weight, adiposity, energy metabolism or circulating corticosterone levels. Taken together, this work describes the first NPY-based anabolic treatment for improving bone mass, and highlights the therapeutic potential of blocking Y1 receptor signalling for the prevention of, or recovery from, degenerative skeletal diseases. © 2012 Elsevier Inc.
Keywords: animal experiment; animal tissue; Animals; Arginine; article; body weight; Bone Density; bone mass; bone metabolism; bone strength; cancellous bone; controlled study; cortical bone; corticosterone; corticosterone blood level; dose response; Dose-Response Relationship, Drug; drug effect; drug mechanism; drug megadose; energy metabolism; femur; food intake; glucose; glucose homeostasis; Homeostasis; male; Mice; Mice, Inbred C57BL; morphometrics; mouse; n2 diphenylacetyl n (4 ureidomethylbenzyl)argininamide; neuropeptide Y; Neuropeptide yY; nonhuman; obesity; Oral drug administration; osteoblast; osteoclast activity; Osteogenesis; osteolysis; Osteopenia; Receptors, Neuropeptide Y; signal transduction; trabecular bone; Y1 receptor antagonism

A novel nanoparticle delivery system for in vivo targeting of the sciatic nerve: Impact on regeneration - Gonçalves, N.P.; Oliveira, H.; Pêgo, A.P.; Saraiva, M.J. (NanomedicineNanomedicine, 2012)
Aim: Innovative solutions in the development of drug delivery systems targeting the nerve tissue are awaited. In this regard, a novel system for the delivery of drugs to the sciatic nerve was created using nanomedical principles. Materials & methods: Chitosan was the vehicle material used in the experiment. Heparin bound to growth factors has been administered to enhance peripheral nerve regeneration, and since heparin possesses the appropriate charge to be able to form nanoparticles with chitosan, it appears to be a good candidate to base this new delivery system on. Results: Maximal absorption took place throughout the extracellular matrix at day 15. No major inflammatory response was observed, indicating that this is a safe and biocompatible system for drug delivery to nerves. Sensorimotor performance and nerve regeneration of mice receiving these nanoparticles were superior as compared with controls. Conclusion: Our work demonstrates a versatile nanoparticle delivery system that successfully targets drugs 'in vivo to the sciatic nerve, opening novel avenues in the field of nanomedicine to the design of therapeutic strategies that enhance axonal regeneration. © 2012 Future Medicine Ltd.
Keywords: chitosan; drug delivery system; heparin; nanomedicine; nanoparticles; peripheral nerve regeneration; sciatic nerve

Preparation and characterization of collagen-nanohydroxyapatite biocomposite scaffolds by cryogelation method for bone tissue engineering applications - Rodrigues, S.C.; Salgado, C.L.; Sahu, A.; Garcia, M.P.; Fernandes, M.H.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2012)
Recent efforts of bone repair focus on development of porous scaffolds for cell adhesion and proliferation. Collagen-nanohydroxyapatite (HA) scaffolds (70:30; 50:50; and 30:70 mass percentage) were produced by cryogelation technique using 1-ethyl-3-(3-dimethyl aminopropyl) carbodiimide hydrochloride/N-hydroxysuccinimide as crosslinking agents. A pure collagen scaffold was used as control. Morphology analysis revealed that all cryogels had highly porous structure with interconnective porosity and the nanoHA aggregates were randomly dispersed throughout the scaffold structure. Chemical analysis showed the presence of all major peaks related to collagen and HA in the biocomposites and indicated possible interaction between nanoHA aggregates and collagen molecules. Porosity analysis revealed an enhancement in the surface area as the nanoHA percentage increased in the collagen structure. The biocomposites showed improved mechanical properties as the nanoHA content increased in the scaffold. As expected, the swelling capacity decreased with the increase of nanoHA content. In vitro studies with osteoblasts cells showed that they were able to attach and spread in all cryogels surfaces. The presence of collagen-nanoHA biocomposites resulted in higher overall cellular proliferation compared to pure collagen scaffold. A statistically significant difference between collagen and collagen-nanoHA cryogels was observed after 21 day of cell culture. These innovative collagen-nanoHA cryogels could have potentially appealing application as scaffolds for bone regeneration. © 2012 Wiley Periodicals, Inc.
Keywords: Biomaterials; Bone tissue engineering; Collagen; Cryogels; Nanohydroxyapatite

Regenerative medicine for the treatment of spinal cord injury: More than just promises? - Pêgo, A.P.; Kubinova, S.; Cizkova, D.; Vanicky, I.; Mar, F.M.; Sousa, M.M.; Sykova, E. (Journal of Cellular and Molecular MedicineJ. Cell. Mol. Med., 2012)
Spinal cord injury triggers a complex set of events that lead to tissue healing without the restoration of normal function due to the poor regenerative capacity of the spinal cord. Nevertheless, current knowledge about the intrinsic regenerative ability of central nervous system axons, when in a supportive environment, has made the prospect of treating spinal cord injury a reality. Among the range of strategies under investigation, cell-based therapies offer the most promising results, due to the multifactorial roles that these cells can fulfil. However, the best cell source is still a matter of debate, as are clinical issues that include the optimal cell dose as well as the timing and route of administration. In this context, the role of biomaterials is gaining importance. These can not only act as vehicles for the administered cells but also, in the case of chronic lesions, can be used to fill the permanent cyst, thus creating a more favourable and conducive environment for axonal regeneration in addition to serving as local delivery systems of therapeutic agents to improve the regenerative milieu. Some of the candidate molecules for the future are discussed in view of the knowledge derived from studying the mechanisms that facilitate the intrinsic regenerative capacity of central nervous system neurons. The future challenge for the multidisciplinary teams working in the field is to translate the knowledge acquired in basic research into effective combinatorial therapies to be applied in the clinic. © 2012 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
Keywords: Biomaterials; Cell therapies; Clinical trials; Conditioning lesion; Gene therapy; Growth factors; Spinal cord injury; Stem cells

Tumor cell-educated periprostatic adipose tissue acquires an aggressive cancer-promoting secretory profile - Ribeiro, R.J.T.; Monteiro, C.P.D.; Cunha, V.F.P.M.; Azevedo, A.S.M.; Oliveira, M.J.; Monteiro, R.; Fraga, A.M.; Príncipe, P.; Lobato, C.; Lobo, F.; Morais, A.; Silva, V.; et al. (Cellular Physiology and BiochemistryCell. Physiol. Biochem., 2012)
Background/Aims: The microenvironment produces important factors that are crucial to prostate cancer (PCa) progression. However, the extent to which the cancer cells stimulate periprostatic adipose tissue (PPAT) to produce these proteins is largely unknown. Our purpose was to determine whether PCa cell-derived factors influence PPAT metabolic activity. Methods: Primary cultures of human PPAT samples from PCa patients (adipose tissue organotypic explants and primary stromal vascular fraction, SVF) were stimulated with conditioned medium (CM) collected from prostate carcinoma (PC3) cells. Cultures without CM were used as control. We used multiplex analysis and ELISA for protein quantification, qPCR to determine mitochondrial DNA (mtDNA) copy number and zymography for matrix metalloproteinase activity, in order to evaluate the response of adipose tissue explants and SVFs to PC3 CM. Results: Stimulation of PPAT explants with PCa PC3 CM induced adipokines associated with cancer progression (osteopontin, tumoral necrosis factor alpha and interleukin-6) and reduced the expression of the protective adipokine adiponectin. Notably, osteopontin protein expression was 13-fold upregulated. Matrix metalloproteinase 9 activity and mitochondrial DNA copy number were higher after stimulation with cancer CM. Stromovascular cells from PPAT in culture were not influenced by tumor-derived factors. Conclusion: The modulation of adipokine expression by tumor CM indicates the pervasive extent to which tumor cells command PPAT to produce factors favorable to their aggressiveness. © 2012 S. Karger AG, Basel.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: CEPBEdoi: 10.1159/000337604PubMed ID: 22415092Language of Original Document: EnglishCorrespondence Address: Ribeiro, R.J.T.; Portuguese Institute of Oncology, Porto Centre Molecular Oncology Group -CI, Edifício Laboratórios -Piso 4, Rua Dr. António Bernardino Almeida, 4200-072 Porto, Portugal; email: oriebir.r@gmail.comChemicals/CAS: adiponectin, 283182-39-8; gelatinase B, 146480-36-6; osteopontin, 106441-73-0; Adiponectin; Culture Media, Conditioned; Cytokines; DNA, Mitochondrial; Interleukin-6; Matrix Metalloproteinase 2, 3.4.24.24; Matrix Metalloproteinase 9, 3.4.24.35; Osteopontin, 106441-73-0; Tumor Necrosis Factor-alphaReferences: Hsing, A.W., Sakoda, L.C., Chua Jr., S., Obesity, metabolic syndrome, and prostate cancer (2007) Am J Clin Nutr, 86, pp. s843-857;Cao, Y., Ma, J., Body mass index, prostate cancer-specific mortality, and biochemical recurrence: A systematic review and meta-analysis (2011) Cancer Prev Res (Phila), 4, pp. 486-501; Baillargeon, J., Rose, D.P., Obesity, adipokines, and prostate cancer (review) (2006) Int J Oncol, 28, pp. 737-745; Mistry, T., Digby, J.E., Desai, K.M., Randeva, H.S., Obesity and Prostate Cancer: A Role for Adipokines (2007) European Urology, 52 (1), pp. 46-53. , DOI 10.1016/j.eururo.2007.03.054, PII S0302283807004307; Hirano, T., Morii, H., Nakazawa, K., Murakami, D., Yamashita, A., Asahi, J., Orimo, H., Tokura, Y., Enhancement of adipogenesis induction by conditioned media obtained from cancer cells (2008) Cancer Lett, 268, pp. 286-294; Andarawewa, K.L., Motrescu, E.R., Chenard, M.-P., Gansmuller, A., Stoll, I., Tomasetto, C., Rio, M.-C., Stromelysin-3 is a potent negative regulator of adipogenesis participating to cancer cell-adipocyte interaction/crosstalk at the tumor invasive front (2005) Cancer Research, 65 (23), pp. 10862-10871. , DOI 10.1158/0008-5472.CAN-05-1231; Jotzu, C., Alt, E., Welte, G., Li, J., Hennessy, B.T., Devarajan, E., Krishnappa, S., Song, Y.H., Adipose tissue derived stem cells differentiate into carcinoma-associated fibroblast-like cells under the influence of tumor derived factors (2011) Cell Oncol (Dordr), 34, pp. 55-67; Dolinkova, M., Dostalova, I., Lacinova, Z., Michalsky, D., Haluzikova, D., Mraz, M., The endocrine profile of subcutaneous and visceral adipose tissue of obese patients (2008) Mol Cell Endocrinol, 291, pp. 63-70; Van Roermund, J.G., Hinnen, K.A., Tolman, C.J., Bol, G.H., Witjes, J.A., Bosch, J.L., Kiemeney, L.A., Van Vulpen, M., Periprostatic fat correlates with tumour aggressiveness in prostate cancer patients (2011) BJU Int, 107, pp. 1775-1779; Sumitomo, M., Asakuma, J., Yoshii, H., Sato, A., Horiguchi, A., Ito, K., Nagakura, K., Asano, T., Anterior perirectal fat tissue thickness is a strong predictor of recurrence after high-intensity focused ultrasound for prostate cancer (2010) Int J Urol, 17, pp. 776-782; Finley, D.S., Calvert, V.S., Inokuchi, J., Lau, A., Narula, N., Petricoin, E.F., Zaldivar, F., Ornstein, D.K., Periprostatic adipose tissue as a modulator of prostate cancer aggressiveness (2009) J Urol, 182, pp. 1621-1627; Thalmann, S., Juge-Aubry, C.E., Meier, C.A., Explant cultures of white adipose tissue (2008) Methods Mol Biol, 456, pp. 195-199; Song, G.J., Lewis, V., Mitochondrial DNA integrity and copy number in sperm from infertile men (2008) Fertil Steril, 90, pp. 2238-2244; Park, J., Euhus, D.M., Scherer, P.E., Paracrine and Endocrine Effects of Adipose Tissue on Cancer Development and Progression (2011) Endocr Rev, 32, pp. 550-570; George, D.J., Halabi, S., Shepard, T.F., Sanford, B., Vogelzang, N.J., Small, E.J., Kantoff, P.W., The prognostic significance of plasma interleukin-6 levels in patients with metastatic hormone-refractory prostate cancer: Results from cancer and leukemia group B 9480 (2005) Clinical Cancer Research, 11 (5), pp. 1815-1820. , DOI 10.1158/1078-0432.CCR-04-1560; Michalaki, V., Syrigos, K., Charles, P., Waxman, J., Serum levels of IL-6 and TNF-α correlate with clinicopathological features and patient survival in patients with prostate cancer (2004) British Journal of Cancer, 90 (12), pp. 2312-2316; Dirat, B., Bochet, L., Dabek, M., Daviaud, D., Dauvillier, S., Majed, B., Wang, Y.Y., Muller, C., Cancerassociated adipocytes exhibit an activated phenotype and contribute to breast cancer invasion (2011) Cancer Res, 71, pp. 2455-2465; Culig, Z., New insights into the role of interleukin-6 in human prostate cancer (2009) J Urol, 182, pp. 1255-1256; Chun, J.Y., Nadiminty, N., Dutt, S., Lou, W., Yang, J.C., Kung, H.J., Evans, C.P., Gao, A.C., Interleukin-6 regulates androgen synthesis in prostate cancer cells (2009) Clin Cancer Res, 15, pp. 4815-4822; Weber, G.F., Lett, G.S., Haubein, N.C., Osteopontin is a marker for cancer aggressiveness and patient survival (2010) Br J Cancer, 103, pp. 861-869; Thalmann, G.N., Sikes, R.A., Devoll, R.E., Kiefer, J.A., Markwalder, R., Klima, I., Farach-Carson, C.M., Chung, L.W.K., Osteopontin: Possible role in prostate cancer progression (1999) Clinical Cancer Research, 5 (8), pp. 2271-2277; McAllister, S.S., Gifford, A.M., Greiner, A.L., Kelleher, S.P., Saelzler, M.P., Ince, T.A., Reinhardt, F., Weinberg, R.A., Systemic Endocrine Instigation of Indolent Tumor Growth Requires Osteopontin (2008) Cell, 133 (6), pp. 994-1005. , DOI 10.1016/j.cell.2008.04.045, PII S0092867408006211; Balkwill, F., TNF-alpha in promotion and progression of cancer (2006) Cancer Metastasis Rev, 25, pp. 409-416; Yan, B., Wang, H., Rabbani, Z.N., Zhao, Y., Li, W., Yuan, Y., Li, F., Li, C.-Y., Tumor necrosis factor-α is a potent endogenous mutagen that promotes cellular transformation (2006) Cancer Research, 66 (24), pp. 11565-11570. , DOI 10.1158/0008-5472.CAN-06-2540; Bates, R.C., Mercurio, A.M., Tumor necrosis factor-α stimulates the epithelial-tomesenchymal transition of human colonic organoids (2003) Molecular Biology of the Cell, 14 (5), pp. 1790-1800. , DOI 10.1091/mbc.E02-09-0583; Yamauchi, T., Kamon, J., Waki, H., Terauchi, Y., Kubota, N., Hara, K., Mori, Y., Kadowaki, T., The fat-derived hormone adiponectin reverses insulin resistance associated with both lipoatrophy and obesity (2001) Nature Medicine, 7 (8), pp. 941-946. , DOI 10.1038/90984; Li, H., Stampfer, M.J., Mucci, L., Rifai, N., Qiu, W., Kurth, T., Ma, J., A 25-year prospective study of plasma adiponectin and leptin concentrations and prostate cancer risk and survival (2010) Clin Chem, 56, pp. 34-43; Ribeiro, R., Lopes, C., Medeiros, R., The link between obesity and prostate cancer: The leptin pathway and therapeutic perspectives (2006) Prostate Cancer and Prostatic Diseases, 9 (1), pp. 19-24. , DOI 10.1038/sj.pcan.4500844, PII 4500844; Vaday, G.G., Peehl, D.M., Kadam, P.A., Lawrence, D.M., Expression of CCL5 (RANTES) and CCR5 in prostate cancer (2006) Prostate, 66 (2), pp. 124-134. , DOI 10.1002/pros.20306; Kessenbrock, K., Plaks, V., Werb, Z., Matrix metalloproteinases: Regulators of the tumor microenvironment (2010) Cell, 141, pp. 52-67; Bouloumie, A., Sengenes, C., Portolan, G., Galitzky, J., Lafontan, M., Adipocyte Produces Matrix Metalloproteinases 2 and 9 Involvement in Adipose Differentiation (2001) Diabetes, 50 (9), pp. 2080-2086; Bergers, G., Brekken, R., McMahon, G., Vu, T.H., Itoh, T., Tamaki, K., Tanzawa, K., Hanahan, D., Matrix metalloproteinase-9 triggers the angiogenic switch during carcinogenesis (2000) Nat Cell Biol, 2, pp. 737-744; Lin, C.Y., Tsai, P.H., Kandaswami, C.C., Lee, P.P., Huang, C.J., Hwang, J.J., Lee, M.T., Matrix metalloproteinase-9 cooperates with transcription factor Snail to induce epithelial-mesenchymal transition (2011) Cancer Sci, 102, pp. 815-827; Chakrabarti, S., Patel, K.D., Matrix metalloproteinase-2 (MMP-2) and MMP-9 in pulmonary pathology (2005) Experimental Lung Research, 31 (6), pp. 599-621. , DOI 10.1080/019021490944232; Sehgal, G., Hua, J., Bernhard, E.J., Sehgal, I., Thompson, T.C., Muschel, R.J., Requirement for matrix metalloproteinase-9 (Gelatinase B) expression in metastasis by murine prostate carcinoma (1998) American Journal of Pathology, 152 (2), pp. 591-596; Johnson, T.R., Koul, S., Kumar, B., Khandrika, L., Venezia, S., Maroni, P.D., Meacham, R.B., Koul, H.K., Loss of PDEF, a prostatederived Ets factor is associated with aggressive phenotype of prostate cancer: Regulation of MMP 9 by PDEF (2010) Mol Cancer, 9, p. 148; Trudel, D., Fradet, Y., Meyer, F., Tetu, B., Matrix metalloproteinase 9 is associated with Gleason score in prostate cancer but not with prognosis (2010) Hum Pathol, 41, pp. 1694-1701; Zhang, L., Shi, J., Feng, J., Klocker, H., Lee, C., Zhang, J., Type IV collagenase (matrix metalloproteinase-2 and -9) in prostate cancer (2004) Prostate Cancer and Prostatic Diseases, 7 (4), pp. 327-332. , DOI 10.1038/sj.pcan.4500750, PII 4500750; Zhong, W.D., Han, Z.D., He, H.C., Bi, X.C., Dai, Q.S., Zhu, G., Ye, Y.K., Chen, Z.N., CD147, MMP-1, MMP-2 and MMP-9 protein expression as significant prognostic factors in human prostate cancer (2008) Oncology, 75, pp. 230-236; Sauer, C.G., Kappeler, A., Spath, M., Kaden, J.J., Michel, M.S., Mayer, D., Bleyl, U., Grobholz, R., Expression and activity of matrix metalloproteinases-2 and -9 in serum, core needle biopsies and tissue specimens of prostate cancer patients (2004) Virchows Archiv, 444 (6), pp. 518-526; Opdenakker, G., Masure, S., Grillet, B., Van Damme, J., Cytokine-mediated regulation of human leukocyte gelatinases and role in arthritis (1991) Lymphokine Cytokine Res, 10, pp. 317-324; Unal, R., Yao-Borengasser, A., Varma, V., Rasouli, N., Labbate, C., Kern, P.A., Ranganathan, G., Matrix metalloproteinase-9 is increased in obese subjects and decreases in response to pioglitazone (2010) J Clin Endocrinol Metab, 95, pp. 2993-3001; Catalan, V., Gomez-Ambrosi, J., Rodriguez, A., Ramirez, B., Silva, C., Rotellar, F., Gil, M.J., Frühbeck, G., Increased adipose tissue expression of lipocalin-2 in obesity is related to inflammation and matrix metalloproteinase-2 and metalloproteinase-9 activities in humans (2009) J Mol Med (Berl), 87, pp. 803-813; Villarroya, J., Giralt, M., Villarroya, F., Mitochondrial DNA: An up-and-coming actor in white adipose tissue pathophysiology (2009) Obesity (Silver Spring), 17, pp. 1814-1820; Robin, E.D., Wong, R., Mitochondrial DNA molecules and virtual number of mitochondria per cell in mammalian cells (1988) J Cell Physiol, 136, pp. 507-513; Kaaman, M., Sparks, L.M., Van Harmelen, V., Smith, S.R., Sjolin, E., Dahlman, I., Arner, P., Strong association between mitochondrial DNA copy number and lipogenesis in human white adipose tissue (2007) Diabetologia, 50 (12), pp. 2526-2533. , DOI 10.1007/s00125-007-0818-6; Yamauchi, T., Kamon, J., Waki, H., Murakami, K., Motojima, K., Komeda, K., Ide, T., Kadowaki, T., The mechanisms by which both heterozygous peroxisome proliferator- activated receptor gamma (PPARgamma) deficiency and PPARgamma agonist improve insulin resistance (2001) J Biol Chem, 276, pp. 41245-41254; Wilson-Fritch, L., Burkart, A., Bell, G., Mendelson, K., Leszyk, J., Nicoloro, S., Czech, M., Corvera, S., Mitochondrial biogenesis and remodeling during adipogenesis and in response to the insulin sensitizer rosiglitazone (2003) Molecular and Cellular Biology, 23 (3), pp. 1085-1094. , DOI 10.1128/MCB.23.3.1085-1094.2003; Ducluzeau, P.H., Priou, M., Weitheimer, M., Flamment, M., Duluc, L., Iacobazi, F., Soleti, R., Malthièry, Y., Dynamic regulation of mitochondrial network and oxidative functions during 3T3-L1 fat cell differentiation (2011) J Physiol Biochem, 67, pp. 285-296; Bogacka, I., Ukropcova, B., McNeil, M., Gimble, J.M., Smith, S.R., Structural and functional consequences of mitochondrial biogenesis in human adipocytes in vitro (2005) Journal of Clinical Endocrinology and Metabolism, 90 (12), pp. 6650-6656. , http://jcem.endojournals.org/cgi/reprint/90/12/6650, DOI 10.1210/jc.2005-1024; Toda, S., Uchihashi, K., Aoki, S., Sonoda, E., Yamasaki, F., Piao, M., Ootani, A., Sugihara, H., Adipose tissueorganotypic culture system as a promising model for studying adipose tissue biology and regeneration (2009) Organogenesis, 5, pp. 50-56; Tuxhorn, J.A., Ayala, G.E., Rowley, D.R., Reactive stroma in prostate cancer progression (2001) Journal of Urology, 166 (6), pp. 2472-2483
Keywords: Adipokines; adiponectin; adipose tissue; adult; article; cancer cell; cancer growth; Cells, Cultured; clinical article; controlled study; Culture Media, Conditioned; culture medium; Cytokines; DNA, Mitochondrial; enzyme activity; enzyme linked immunosorbent assay; explant; gelatinase B; human; human cell; human tissue; Humans; interleukin 6; Interleukin-6; male; Matrix Metalloproteinase 2; Matrix Metalloproteinase 9; Middle Aged; mitochondrial DNA; Osteopontin; Periprostatic adipose tissue; priority journal; Prostate cancer; Prostatic Neoplasms; protein expression; protein induction; protein secretion; quantitative analysis; stroma cell; tissue metabolism; tumor necrosis factor alpha; Tumor Necrosis Factor-alpha

The Arabidopsis D-Type Cyclin CYCD2;1 and the Inhibitor ICK2/KRP2 Modulate Auxin-Induced Lateral Root Formation - Sanz, L.; Dewitte, W.; Forzani, C.; Patell, F.; Nieuwland, J.; Wen, B.; Quelhas, P.; de Jager, S.; Titmus, C.; Campilho, A.; Ren, H.; Estelle, M.; et al. (Plant CellPlant Cell, 2011)
The integration of cell division in root growth and development requires mediation of developmental and physiological signals through regulation of cyclin-dependent kinase activity. Cells within the pericycle form de novo lateral root meristems, and D-type cyclins (CYCD), as regulators of the G 1-to-S phase cell cycle transition, are anticipated to play a role. Here, we show that the D-type cyclin protein CYCD2;1 is nuclear in Arabidopsis thaliana root cells, with the highest concentration in apical and lateral meristems. Loss of CYCD2;1 has a marginal effect on unstimulated lateral root density, but CYCD2;1 is rate-limiting for the response to low levels of exogenous auxin. However, while CYCD2;1 expression requires sucrose, it does not respond to auxin. The protein Inhibitor-Interactor of CDK/Kip Related Protein2 (ICK2/KRP2), which interacts with CYCD2;1, inhibits lateral root formation, and ick2/krp2 mutants show increased lateral root density. ICK2/ KRP2 can modulate the nuclear levels of CYCD2;1, and since auxin reduces ICK2/KRP2 protein levels, it affects both activity and cellular distribution of CYCD2;1. Hence, as ICK2/KRP2 levels decrease, the increase in lateral root density depends on CYCD2;1, irrespective of ICK2/CYCD2;1 nuclear localization. We propose that ICK2/KRP2 restrains root ramification by maintaining CYCD2;1 inactive and that this modulates pericycle responses to auxin fluctuations. © 2011 American Society of Plant Biologists.
Cited By (since 1996): 14Export Date: 21 November 2012Source: ScopusCODEN: PLCEEdoi: 10.1105/tpc.110.080002PubMed ID: 21357490Language of Original Document: EnglishCorrespondence Address: Murray, J. A. H.; Cardiff School of Biosciences, Cardiff University, CF10 3AX Cardiff, United Kingdom; email: murrayja1@cardiff.ac.ukChemicals/CAS: proteasome, 140879-24-9; ATP dependent 26S protease, 3.4.99.-; Arabidopsis Proteins; Cell Cycle Proteins; CycD2 protein, Arabidopsis; Cyclins; ICK2 protein, Arabidopsis; Indoleacetic Acids; Proteasome Endopeptidase Complex, 3.4.25.1References: Achard, P., Gusti, A., Cheminant, S., Alioua, M., Dhondt, S., Coppens, F., Beemster, G.T., Genschik, P., Gibberellin signaling controls cell proliferation rate in Arabidopsis (2009) Curr. Biol., 19, pp. 1188-1193;Alonso, J.M., Genome-wide insertional mutagenesis of Arabidopsis thaliana (2003) Science, 301, pp. 653-657; Baluska, F., Mancuso, S., Volkmann, D., Barlow, P.W., Root apex transition zone: A signalling-response nexus in the root (2010) Trends Plant Sci., 15, pp. 402-408; Bechtold, N., Pelletier, G., In planta Agrobacterium-mediated transformation of adult Arabidopsis thaliana plants by vacuum infiltration (1998) Methods Mol. Biol., 82, pp. 259-266; Bird, D.A., Buruiana, M.M., Zhou, Y., Fowke, L.C., Wang, H., Arabidopsis cyclin-dependent kinase inhibitors are nuclearlocalized and show different localization patterns within the nucleoplasm (2007) Plant Cell Rep., 26, pp. 861-872; Boerjan, W., Cervera, M.T., Delarue, M., Beeckman, T., Dewitte, W., Bellini, C., Caboche, M., Inzé, D., Superroot, a recessive mutation in Arabidopsis, confers auxin overproduction (1995) Plant Cell, 7, pp. 1405-1419; Boisnard-Lorig, C., Colon-Carmona, A., Bauch, M., Hodge, S., Doerner, P., Bancharel, E., Dumas, C., Berger, F., Dynamic analyses of the expression of the HISTONE:YFP fusion protein in Arabidopsis show that syncytial endosperm is divided in mitotic domains (2001) Plant Cell, 13, pp. 495-509; Boniotti, M.B., Gutierrez, C., A cell-cycle-regulated kinase activity phosphorylates plant retinoblastoma protein and contains, in Arabidopsis, a CDKA/cyclin D complex (2001) Plant J., 28, pp. 341-350; Boruc, J., Van den Daele, H., Hollunder, J., Rombauts, S., Mylle, E., Hilson, P., Inzé, D., Russinova, E., Functional modules in the Arabidopsis core cell cycle binary proteinprotein interaction network (2010) Plant Cell, 22, pp. 1264-1280; Brady, S.M., Orlando, D.A., Lee, J.Y., Wang, J.Y., Koch, J., Dinneny, J.R., Mace, D., Benfey, P.N., A high-resolution root spatiotemporal map reveals dominant expression patterns (2007) Science, 318, pp. 801-806; Casimiro, I., Beeckman, T., Graham, N., Bhalerao, R., Zhang, H., Casero, P., Sandberg, G., Bennett, M.J., Dissecting Arabidopsis lateral root development (2003) Trends Plant Sci., 8, pp. 165-171; Casimiro, I., Marchant, A., Bhalerao, R.P., Beeckman, T., Dhooge, S., Swarup, R., Graham, N., Bennett, M., Auxin transport promotes Arabidopsis lateral root initiation (2001) Plant Cell, 13, pp. 843-852; Chevray, P.M., Nathans, D., Protein interaction cloning in yeast: Identification of mammalian proteins that react with the leucine zipper of Jun (1992) Proc. Natl. Acad. Sci. USA, 89, pp. 5789-5793; Churchman, M.L., SIAMESE, a plant-specific cell cycle regulator, controls endoreplication onset in Arabidopsis thaliana (2006) Plant Cell, 18, pp. 3145-3157; Cleary, A., Fowke, L., Wang, H., John, P., The effect of ICK1, a plant cyclin-dependent kinase inhibitor, on mitosis in living plant cells (2002) Plant Cell Rep., 20, pp. 814-820; Clough, S.J., Bent, A.F., Floral dip: A simplified method for Agrobacterium-mediated transformation of Arabidopsis thaliana (1998) Plant J., 16, pp. 735-743; Cockcroft, C.E., den Boer, B.G., Healy, J.M., Murray, J.A.H., Cyclin D control of growth rate in plants (2000) Nature, 405, pp. 575-579; de Smet, I., Vanneste, S., Inzé, D., Beeckman, T., Lateral root initiation or the birth of a new meristem (2006) Plant Mol. Biol., 60, pp. 871-887; de Smet, I., Auxin-dependent regulation of lateral root positioning in the basal meristem of Arabidopsis (2007) Development, 134, pp. 681-690; de Smet, I., Bimodular auxin response controls organogenesis (2010) Proc. Natl. Acad. Sci. USA, 107, pp. 2705-2710; de Veylder, L., Beeckman, T., Beemster, G.T., de Almeida Engler, J., Ormenese, S., Maes, S., Naudts, M., Inzé, D., Control of proliferation, endoreduplication and differentiation by the Arabidopsis E2Fa-DPa transcription factor (2002) EMBO J., 21, pp. 1360-1368; de Veylder, L., Beeckman, T., Beemster, G.T., Krols, L., Terras, F., Landrieu, I., van der Schueren, E., Inzé, D., Functional analysis of cyclin-dependent kinase inhibitors of Arabidopsis (2001) Plant Cell, 13, pp. 1653-1668; de Veylder, L., de Almeida Engler, J., Burssens, S., Manevski, A., Lescure, B., Van Montagu, M., Engler, G., Inzé, D., A new D-type cyclin of Arabidopsis thaliana expressed during lateral root primordia formation (1999) Planta, 208, pp. 453-462; Dewitte, W., Murray, J.A.H., The plant cell cycle (2003) Annu. Rev. Plant Biol., 54, pp. 235-264; Dewitte, W., Riou-Khamlichi, C., Scofield, S., Healy, J.M., Jacqmard, A., Kilby, N.J., Murray, J.A.H., Altered cell cycle distribution, hyperplasia, and inhibited differentiation in Arabidopsis caused by the D-type cyclin CYCD3 (2003) Plant Cell, 15, pp. 79-92; Dewitte, W., Scofield, S., Alcasabas, A.A., Maughan, S.C., Menges, M., Braun, N., Collins, C., Murray, J.A.H., Arabidopsis CYCD3 D-type cyclins link cell proliferation and endocycles and are rate-limiting for cytokinin responses (2007) Proc. Natl. Acad. Sci. USA, 104, pp. 14537-14542; Dharmasiri, N., Dharmasiri, S., Weijers, D., Karunarathna, N., Jurgens, G., Estelle, M., AXL and AXR1 have redundant functions in RUB conjugation and growth and development in Arabidopsis (2007) Plant J., 52, pp. 114-123; Ditengou, F.A., Teale, W.D., Kochersperger, P., Flittner, K.A., Kneuper, I., van der Graaff, E., Nziengui, H., Palme, K., Mechanical induction of lateral root initiation in Arabidopsis thaliana (2008) Proc. Natl. Acad. Sci. USA, 105, pp. 18818-18823; Dubrovsky, J.G., Rost, T.L., Colón-Carmona, A., Doerner, P., Early primordium morphogenesis during lateral root initiation in Arabidopsis thaliana (2001) Planta, 214, pp. 30-36; Dubrovsky, J.G., Sauer, M., Napsucialy-Mendivil, S., Ivanchenko, M.G., Friml, J., Shishkova, S., Celenza, J., Benková, E., Auxin acts as a local morphogenetic trigger to specify lateral root founder cells (2008) Proc. Natl. Acad. Sci. USA, 105, pp. 8790-8794; Duttweiler, H.M., A highly sensitive and non-lethal beta-galactosidase plate assay for yeast (1996) Trends Genet., 12, pp. 340-341; Ebel, C., Mariconti, L., Gruissem, W., Plant retinoblastoma homologues control nuclear proliferation in the female gametophyte (2004) Nature, 429, pp. 776-780; Fukaki, H., Tameda, S., Masuda, H., Tasaka, M., Lateral root formation is blocked by a gain-of-function mutation in the SOLITARY-ROOT/IAA14 gene of Arabidopsis (2002) Plant J., 29, pp. 153-168; Fukaki, H., Tasaka, M., Hormone interactions during lateral root formation (2009) Plant Mol. Biol., 69, pp. 437-449; Healy, J.M., Menges, M., Doonan, J.H., Murray, J.A.H., The Arabidopsis D-type cyclins CycD2 and CycD3 both interact in vivo with the PSTAIRE cyclin-dependent kinase Cdc2a but are differentially controlled (2001) J. Biol. Chem., 276, pp. 7041-7047; Himanen, K., Boucheron, E., Vanneste, S., de Almeida Engler, J., Inzé, D., Beeckman, T., Auxin-mediated cell cycle activation during early lateral root initiation (2002) Plant Cell, 14, pp. 2339-2351; Himanen, K., Vuylsteke, M., Vanneste, S., Vercruysse, S., Boucheron, E., Alard, P., Chriqui, D., Beeckman, T., Transcript profiling of early lateral root initiation (2004) Proc. Natl. Acad. Sci. USA, 101, pp. 5146-5151; Hirano, H., Harashima, H., Shinmyo, A., Sekine, M., Arabidopsis RETINOBLASTOMA-RELATED PROTEIN 1 is involved in G1 phase cell cycle arrest caused by sucrose starvation (2008) Plant Mol. Biol., 66, pp. 259-275; Huntley, R., The maize retinoblastoma protein homologue ZmRb-1 is regulated during leaf development and displays conserved interactions with G1/S regulators and plant cyclin D (CycD) proteins (1998) Plant Mol. Biol., 37, pp. 155-169; Inzé, D., De Veylder, L., Cell cycle regulation in plant development (2006) Annu. Rev. Genet., 40, pp. 77-105; Jakoby, M.J., Weinl, C., Pusch, S., Kuijt, S.J., Merkle, T., Dissmeyer, N., Schnittger, A., Analysis of the subcellular localization, function, and proteolytic control of the Arabidopsis cyclin-dependent kinase inhibitor ICK1/KRP1 (2006) Plant Physiol., 141, pp. 1293-1305; James, P., Halladay, J., Craig, E.A., Genomic libraries and a host strain designed for highly efficient two-hybrid selection in yeast (1996) Genetics, 144, pp. 1425-1436; Jasinski, S., Riou-Khamlichi, C., Roche, O., Perennes, C., Bergounioux, C., Glab, N., The CDK inhibitor NtKIS1a is involved in plant development, endoreduplication and restores normal development of cyclin D3;1-overexpressing plants (2002) J. Cell Sci., 115, pp. 973-982; Karimi, M., Depicker, A., Hilson, P., Recombinational cloning with plant gateway vectors (2007) Plant Physiol., 145, pp. 1144-1154; Kohalmi, S.E., Nowak, J., Crosby, W.L., The yeast twohybrid system (1997) Differentially Expressed Genes in Plants: A Bench Manual, pp. 63-82. , In, E. Hansen and G. Harper, eds (London: Taylor & Francis); Laskowski, M., Grieneisen, V.A., Hofhuis, H., Hove, C.A., Hogeweg, P., Marée, A.F., Scheres, B., Root system architecture from coupling cell shape to auxin transport (2008) PLoS Biol., 6, pp. e307; Laskowski, M.J., Williams, M.E., Nusbaum, H.C., Sussex, I.M., Formation of lateral root meristems is a two-stage process (1995) Development, 121, pp. 3303-3310; Lechner, E., Xie, D., Grava, S., Pigaglio, E., Planchais, S., Murray, J.A.H., Parmentier, Y., Genschik, P., The AtRbx1 protein is part of plant SCF complexes, and its down-regulation causes severe growth and developmental defects (2002) J. Biol. Chem., 277, pp. 50069-50080; Lincoln, C., Britton, J.H., Estelle, M., Growth and development of the axr1 mutants of Arabidopsis (1990) Plant Cell, 2, pp. 1071-1080; López-Bucio, J., Cruz-Ramírez, A., Herrera-Estrella, L., The role of nutrient availability in regulating root architecture (2003) Curr. Opin. Plant Biol., 6, pp. 280-287; Marcuzzo, M., Quelhas, P., Campilho, A., Mendonça, A.M., Campilho, A., Automated Arabidopsis plant root cell segmentation based on SVM classification and region merging (2009) Comput. Biol. Med., 39, pp. 785-793; Masubelele, N.H., Dewitte, W., Menges, M., Maughan, S., Collins, C., Huntley, R., Nieuwland, J., Murray, J.A.H., D-type cyclins activate division in the root apex to promote seed germination in Arabidopsis (2005) Proc. Natl. Acad. Sci. USA, 102, pp. 15694-15699; Menges, M., de Jager, S.M., Gruissem, W., Murray, J.A.H., Global analysis of the core cell cycle regulators of Arabidopsis identifies novel genes, reveals multiple and highly specific profiles of expression and provides a coherent model for plant cell cycle control (2005) Plant J., 41, pp. 546-566; Menges, M., Samland, A.K., Planchais, S., Murray, J.A.H., The D-type cyclin CYCD3;1 is limiting for the G1-to-S-phase transition in Arabidopsis (2006) Plant Cell, 18, pp. 893-906; Minet, M., Dufour, M.E., Lacroute, F.B., Complementation of Saccharomyces cerevisiae auxotrophic mutants by Arabidopsis thaliana cDNAs (1992) Plant J., 2, pp. 417-422; Moreno-Risueno, M.A., Van Norman, J.M., Moreno, A., Zhang, J., Ahnert, S.E., Benfey, P.N., Oscillating gene expression determines competence for periodic Arabidopsis root branching (2010) Science, 329, pp. 1306-1311; Nieuwland, J., Maughan, S., Dewitte, W., Scofield, S., Sanz, L., Murray, J.A.H., The D-type cyclin CYCD4;1 modulates lateral root density in Arabidopsis by affecting the basal meristem region (2009) Proc. Natl. Acad. Sci. USA, 106, pp. 22528-22533; Okushima, Y., Fukaki, H., Onoda, M., Theologis, A., Tasaka, M., ARF7 and ARF19 regulate lateral root formation via direct activation of LBD/ASL genes in Arabidopsis (2007) Plant Cell, 19, pp. 118-130; Péret, B., De Rybel, B., Casimiro, I., Benková, E., Swarup, R., Laplaze, L., Beeckman, T., Bennett, M.J., Arabidopsis lateral root development: An emerging story (2009) Trends Plant Sci., 14, pp. 399-408; Petersson, S.V., Johansson, A.I., Kowalczyk, M., Makoveychuk, A., Wang, J.Y., Moritz, T., Grebe, M., Ljung, K., An auxin gradient and maximum in the Arabidopsis root apex shown by high-resolution cell-specific analysis of IAA distribution and synthesis (2009) Plant Cell, 21, pp. 1659-1668; Petroski, M.D., Deshaies, R.J., Function and regulation of cullin-RING ubiquitin ligases (2005) Nat. Rev. Mol. Cell Biol., 6, pp. 9-20; Planchais, S., Samland, A.K., Murray, J.A.H., Differential stability of Arabidopsis D-type cyclins: CYCD3;1 is a highly unstable protein degraded by a proteasome-dependent mechanism (2004) Plant J., 38, pp. 616-625; Qi, R., John, P.C., Expression of genomic AtCYCD2;1 in Arabidopsis induces cell division at smaller cell sizes: Implications for the control of plant growth (2007) Plant Physiol., 144, pp. 1587-1597; Ren, H., Santner, A., del Pozo, J.C., Murray, J.A.H., Estelle, M., Degradation of the cyclin-dependent kinase inhibitor KRP1 is regulated by two different ubiquitin E3 ligases (2008) Plant J., 53, pp. 705-716; Richter, G.L., Monshausen, G.B., Krol, A., Gilroy, S., Mechanical stimuli modulate lateral root organogenesis (2009) Plant Physiol., 151, pp. 1855-1866; Riou-Khamlichi, C., Huntley, R., Jacqmard, A., Murray, J.A.H., Cytokinin activation of Arabidopsis cell division through a D-type cyclin (1999) Science, 283, pp. 1541-1544; Riou-Khamlichi, C., Menges, M., Healy, J.M., Murray, J.A.H., Sugar control of the plant cell cycle: Differential regulation of Arabidopsis D-type cyclin gene expression (2000) Mol. Cell. Biol., 20, pp. 4513-4521; Sabatini, S., Beis, D., Wolkenfelt, H., Murfett, J., Guilfoyle, T., Malamy, J., Benfey, P., Scheres, B., An auxin-dependent distal organizer of pattern and polarity in the Arabidopsis root (1999) Cell, 99, pp. 463-472; Schnittger, A., Schöbinger, U., Bouyer, D., Weinl, C., Stierhof, Y.D., Hülskamp, M., Ectopic D-type cyclin expression induces not only DNA replication but also cell division in Arabidopsis trichomes (2002) Proc. Natl. Acad. Sci. USA, 99, pp. 6410-6415; van Leene, J., Targeted interactomics reveals a complex core cell cycle machinery in Arabidopsis thaliana (2010) Mol. Syst. Biol., 6, p. 397; Vanneste, S., Cell cycle progression in the pericycle is not sufficient for SOLITARY ROOT/IAA14-mediated lateral root initiation in Arabidopsis thaliana (2005) Plant Cell, 17, pp. 3035-3050; Verkest, A., Manes, C.L., Vercruysse, S., Maes, S., van der Schueren, E., Beeckman, T., Genschik, P., De Veylder, L., The cyclin-dependent kinase inhibitor KRP2 controls the onset of the endoreduplication cycle during Arabidopsis leaf development through inhibition of mitotic CDKA;1 kinase complexes (2005) Plant Cell, 17, pp. 1723-1736; Verkest, A., Weinl, C., Inzé, D., De Veylder, L., Schnittger, A., Switching the cell cycle. Kip-related proteins in plant cell cycle control (2005) Plant Physiol., 139, pp. 1099-1106; Wang, H., Qi, Q., Schorr, P., Cutler, A.J., Crosby, W.L., Fowke, L.C., ICK1, a cyclin-dependent protein kinase inhibitor from Arabidopsis thaliana interacts with both Cdc2a and CycD3, and its expression is induced by abscisic acid (1998) Plant J., 15, pp. 501-510; Wildwater, M., Campilho, A., Perez-Perez, J.M., Heidstra, R., Blilou, I., Korthout, H., Chatterjee, J., Scheres, B., The RETINOBLASTOMA-RELATED gene regulates stem cell maintenance in Arabidopsis roots (2005) Cell, 123, pp. 1337-1349; Willemse, J., Kulikova, O., de Jong, H., Bisseling, T., A new whole-mount DNA quantification method and the analysis of nuclear DNA content in the stem-cell niche of Arabidopsis roots (2008) Plant J., 55, pp. 886-894; Winter, D., Vinegar, B., Nahal, H., Ammar, R., Wilson, G.V., Provart, N.J., An "Electronic Fluorescent Pictograph" browser for exploring and analyzing large-scale biological data sets (2007) PLoS ONE, 2, pp. e718; Zhou, Y., Fowke, L.C., Wang, H., Plant CDK inhibitors: Studies of interactions with cell cycle regulators in the yeast twohybrid system and functional comparisons in transgenic Arabidopsis plants (2002) Plant Cell Rep., 20, pp. 967-975; Zhou, Y., Niu, H., Brandizzi, F., Fowke, L.C., Wang, H., Molecular control of nuclear and subnuclear targeting of the plant CDK inhibitor ICK1 and ICK1-mediated nuclear transport of CDKA (2006) Plant Mol. Biol., 62, pp. 261-278; Zhou, Y., Wang, H., Gilmer, S., Whitwill, S., Fowke, L.C., Effects of co-expressing the plant CDK inhibitor ICK1 and D-type cyclin genes on plant growth, cell size and ploidy in Arabidopsis thaliana (2003) Planta, 216, pp. 604-613
Keywords: Arabidopsis; Arabidopsis protein; Arabidopsis Proteins; Arabidopsis thaliana; article; ATP dependent 26S protease; cell cycle; cell cycle protein; Cell Cycle Proteins; cell nucleus; CycD2 protein, Arabidopsis; cycline; Cyclins; gene expression regulation; Gene Expression Regulation, Plant; genetics; growth, development and aging; ICK2 protein, Arabidopsis; indoleacetic acid derivative; Indoleacetic Acids; metabolism; mutation; plant root; Plant roots; proteasome; Proteasome Endopeptidase Complex

Automatic segmentation of chromatographic images for region of interest delineation - Mendonça, A.M.; Sousa, A.V.; Sá-Miranda, M.C.; Campilho, A.C. (Progress in Biomedical Optics and Imaging - Proceedings of SPIEProgr. Biomed. Opt. Imaging Proc. SPIE, 2011)
This paper describes a segmentation method for automating the region of interest (ROI) delineation in chromatographic images, thus allowing the definition of the image area that contains the fundamental information for further processing while excluding the frame of the chromatographic plate that does not contain relevant data for disease identification. This is the first component of a screening tool for Fabry disease, which will be based on the automatic analysis of the chromatographic patterns extracted from the image ROI. Image segmentation is performed in two phases, where each individual pixel is finally considered as frame or ROI. In the first phase, an unsupervised learning method is used for classifying image pixels into three classes: frame, ROI or unknown. In the second phase, distance features are used for deciding which class the unknown pixels belong to. The segmentation result is post-processed using a sequence of morphological operators in order to obtain the final ROI rectangular area. The proposed methodology was successfully evaluated in a dataset of 41 chromatographic images. © 2011 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).
Conference code: 84913Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusArt. No.: 79623Bdoi: 10.1117/12.877671Language of Original Document: EnglishCorrespondence Address: Mendonça, A. M.; Instituto de Engenharia Biomédica, Universidade Do Porto, Rua Dr. Roberto Frias, s/n, 4200-465 Porto, Portugal; email: amendon@fe.up.ptReferences: Zarate, Y., Hopkin, R., Fabry's disease (2008) The Lancet, 372 (9647), pp. 1427-1435;Gerasimov, A.V., Use of the Software Processing of Scanned Chromatogram Images in Quantitative Planar Chromatography (2004) J. of Anal Chem., 59 (4), pp. 348-353; Bajla, I., Hollander, I., Fluch, S., Burg, K., Kollar, M., An alternative method for electrophoretic gel image analysis in the GelMaster software (2005) Comput Methods Programs Biomed, 77 (3), pp. 209-231; Sousa, A.V., Mendonca, A.M., Campilho, A., Chromatographic pattern classification (2008) IEEE Trans on Biomedical Engineering, 55 (6), pp. 1687-1696; Bajla, I., Rublík, F., Arendacká, B., Farkaš, I., Hornišová, K., Štolc, S., Witkovský, V., Segmentation and supervised classification of image objects in Epo doping-control (2009) Machine Vision and Applications, 20 (4), pp. 243-259; Sousa, A.V., Aguiar, R., Mendonça, A.M., Campilho, A., Automatic lane and band detection in images of Thin-Layer Chromatography (2004) LNCS, 3212, pp. 158-216. , Springer; Dempster, A., Laird, N., Rubin, D., Maximum Likelihood from incomplete data via the EM algorithm (1977) J. of the Royal Statistical Society. Series B, 39 (1), pp. 1-38; Heijden, F., Duin, R.P.W., Ridder, D., Tax, D.M.J., (2004) Classification, Parameter Estimation and State Estimation - An Engineering Approach Using Matlab, , John Wiley & Sons Sponsors: The Society of Photo-Optical Instrumentation Engineers (SPIE); Dynasil Corporation/RMD Research; American Association of Physicists in Medicine (AAPM); DQE Instruments, Inc.; Ocean Thin Films, Inc.
Keywords: Automatic analysis; Automatic segmentations; Chromatographic images; Chromatographic plates; Chromatography; Data sets; Distance feature; Fabry disease; Image pixels; Image segmentation; Imaging systems; Medical imaging; Morphological operator; Pixels; Rectangular area; Region of interest; Region of interest delineation; Screening tool; Second phase; Segmentation methods; Segmentation results; Unsupervised learning; Unsupervised learning method

Classification-based segmentation of the region of interest in chromatographic images - Sousa, A.V.; Mendonça, A.M.; Sá-Miranda, M.C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2011)
This paper proposes a classification-based method for automating the segmentation of the region of interest (ROI) in digital images of chromatographic plates. Image segmentation is performed in two phases. In the first phase an unsupervised learning method classifies the image pixels into three classes: frame, ROI or unknown. In the second phase, distance features calculated for the members of the three classes are used for deciding on the new label, ROI or frame, for each individual connected segment previously classified as unknown.The segmentation result is post-processed using a sequence of morphological operators before obtaining the final ROI rectangular area. The proposed methodology, which is the initial step for the development of a screening tool for Fabry disease, was successfully evaluated in a dataset of 58 chromatographic images. © 2011 Springer-Verlag.
Conference code: 85546Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-21596-4_8Language of Original Document: EnglishCorrespondence Address: Sousa, A.V.; Instituto de Engenharia Biomédica, Universidade Do Porto, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: asousa@eu.ipp.ptReferences: Zarate, Y., Hopkin, R., Fabry's Disease (2008) The Lancet, 372 (9647), pp. 1427-1435;Linthorst, G.E., Vedder, A., Aerts, J.M., Hollak, C.E., Screening for Fabry Disease Using Whole Blood Spots Fails to Identify One-third of Female Carriers (2005) Clinica Chimica Acta, 353 (1-2), pp. 201-203; Eng, C.M., Germain, D.P., Banikazemi, M., Warnock, D.G., Wanner, C., Hopkin, R.J., Bultas, J., Wilcox, W.R., Fabry Disease: Guidelines for the Evaluation and Management of Multi-organ System Involvement (2006) Genetics in Medicine, 8 (9), pp. 539-548; Gerasimov, A.V., Use of the Software Processing of Scanned Chromatogram Images in Quantitative Planar Chromatography (2004) J. of Anal. Chem., 59 (4), pp. 348-353; Bajla, I., Hollander, I., Fluch, S., Burg, K., Kollar, M., An Alternative Method for Electrophoretic Gel Image Analysis in the Gelmaster Software (2005) Comput. Methods Programs Biomed., 77 (3), pp. 209-231; Sousa, A.V., Mendonça, A.M., Campilho, A., Chromatographic Pattern Classification (2008) IEEE Trans. on Biomedical Engineering, 55 (6), pp. 1687-1696; Bajla, I., Rublík, F., Arendacká, B., Farkaš, I., Hornišová, K., Štolc, S., Witkovský, V., Segmentation and Supervised Classification of Image Objects in Epo Doping-control (2009) Machine Vision and Applications, 20 (4), pp. 243-259; Sousa, A.V., Aguiar, R., Mendonça, A.M., Campilho, A., Automatic Lane and Band Detection in Images of Thin Layer Chromatography (2004) LNCS, 3212, pp. 158-165. , Campilho, A.C., Kamel, M.S. (eds.) ICIAR 2004. Springer, Heidelberg; Mendonça, A.M., Sousa, A.V., Sá-Miranda, M.C., Campilho, A., Automatic segmentation of chromatographic images for region of interest delineation (2011) SPIE Medical Imaging; Dempster, A., Laird, N., Rubin, D., Maximum Likelihood from Incomplete Data via the EM Algorithm (1997) J. of the Royal Statistical Society. Series B, 39 (1), pp. 1-38; Heijden, F., Robert, P.W.D., Ridder, D., Tax, D.M.J., (2004) Classification, Parameter Estimation and State Estimation, , John Wiley & Sons, Chichester
Keywords: Chromatographic images; Chromatographic plates; Chromatography; Data sets; Digital image; Distance feature; Fabry disease; Image analysis; Image pixels; Image segmentation; Morphological operator; Rectangular area; Region of interest; Region of interest delineation; Screening tool; Second phase; Segmentation results; Unsupervised learning; Unsupervised learning method

Gene delivery into mesenchymal stem cells: A biomimetic approach using rgd nanoclusters based on poly(amidoamine) dendrimers - Pandita, D.; Santos, J.L.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (BiomacromoleculesBiomacromolecules, 2011)
Poly(amidoamine) dendrimers (generations 5 and 6) with amine termini were conjugated with peptides containing the arginine-glycine-aspartic acid (RGD) sequence having in view their application as gene delivery vectors. The idea behind the work was to take advantage of the cationic nature of dendrimers and of the integrin targeting capabilities of the RGD motif to improve gene delivery. Dendrimers were used as scaffolds for RGD clustering and, by controlling the number of peptides (4, 8, and 16) linked to each dendrimer, it was possible to evaluate the effect of RGD density on the gene delivery process. The new vectors were characterized in respect to their ability to neutralize and compact plasmid DNA (pDNA). The complexes formed by the vectors and pDNA were studied concerning their size, zeta potential, capacity of being internalized by cells and ability of transferring genes. Transfection efficiency was analyzed, first, by using a pDNA encoding for Enhanced Green Fluorescent Protein and Firefly Luciferase and, second, by using a pDNA encoding for Bone Morphogenetic Protein-2. Gene expression in mesenchymal stem cells was enhanced using the new vectors in comparison to native dendrimers and was shown to be dependent on the electrostatic interaction established between the dendrimer moiety and the cell surface, as well as on the RGD density of nanoclusters. The use of dendrimer scaffolds for RGD cluster formation is a new approach that can be extended beyond gene delivery applications, whenever RGD clustering is important for modulating cellular responses. © 2011 American Chemical Society.
Cited By (since 1996): 10Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm1012647PubMed ID: 21210673Language of Original Document: EnglishCorrespondence Address: Tomás, H.; CQM-Centro de Química da Madeira, MMRG, Universidade da Madeira, 9000-390 Funchal, Portugal; email: lenat@uma.ptChemicals/CAS: arginylglycylaspartic acid, 99896-85-2; firefly luciferase, 61970-00-1; Dendrimers; Oligopeptides; Poly(amidoamine); Polyamines; arginyl-glycyl-aspartic acid, 99896-85-2References: Pierschbacher, M.D., Ruoslahti, E., (1984) Nature, 309, pp. 30-33;Ruoslahti, E., (1996) Annu. Rev. Cell Dev. Biol., 12, pp. 697-715; Schaffn, P., Dard, M.M., (2003) Cell. Mol. Life Sci., 60, pp. 119-132; Arosio, D., Manzoni, L., Araldi, E.M.V., Caprini, A., Monferini, E., Scolastico, C., (2009) Bioconjugate Chem., 20, pp. 1611-1617; Cai, W., Chen, X., (2008) Nat. Protoc., 3, pp. 89-96; Cai, W., Wu, Y., Chen, K., Cao, Q., Tice, D.A., Chen, X., (2006) Cancer Res., 66, pp. 9673-9681; Gaillard, C., Cellot, G., Li, S., Toma, F.M., Dumortier, H., Spalluto, G., Cacciari, B., Bianco, A., (2009) Adv. Mater., 21, pp. 1-6; Green, J.J., Chiu, E., Leshchiner, E.S., Shi, J., Langer, R., Anderson, D.G., (2007) Nano Lett., 7, pp. 874-879; Hwang, D.S., Sim, S.B., Cha, H.J., (2007) Biomaterials, 28, pp. 4039-4046; Irvine, D.J., Mayes, A.M., Griffith, L.G., (2001) Biomacromolecules, 2, pp. 85-94; Kong, H.J., Hsiong, S., Mooney, D.J., (2007) Nano Lett., 7, pp. 161-166; Lesniak, W.G., Kariapper, M.S., Nair, B.M., Tan, W., Hutson, A., Balogh, L.P., Khan, M.K., (2007) Bioconjugate Chem., 18, pp. 1148-1154; Ng, Q.K., Sutton, M.K., Soonsawad, P., Xing, L., Cheng, H., Segura, T., (2009) Mol. Ther., 17, pp. 828-836; Suk, J.S., Suh, J., Choy, K., Lai, S.K., Fu, J., Hanes, J., (2006) Biomaterials, 27, pp. 5143-5150; Sun, Y.X., Zeng, X., Meng, Q.F., Zhang, X.Z., Cheng, S.X., Zhuo, R.X., (2008) Biomaterials, 29, pp. 4356-4365; Yang, H., Kao, W.J., (2007) Int. J. Nanomed., 2, pp. 89-99; Yoshimoto, M., Ogawa, K., Washiyama, K., Shikano, N., Mori, H., Amano, R., Kawai, K., (2008) Int. J. Cancer, 123, pp. 709-715; Bidarra, S.J., Barrias, C.C., Barbosa, M.A., Soares, R., Granja, P.L., (2010) Biomacromolecules, 11, pp. 1956-1964; Grellier, M., Granja, P.L., Fricain, J.-C., Bidarra, S.J., Renard, M., Bareille, R., Bourget, C., Barbosa, M.A., (2009) Biomaterials, 30, pp. 3271-8; Evangelista, M.B., Hsiong, S., Fernandes, R., Sampaio, P., Kong, H.J., Barrias, C.C., Salema, R., Granja, P.L., (2007) Biomaterials, 28, pp. 3644-55; Alsberg, E., Anderson, K.W., Albeiruti, A., Franceschi, R.T., Mooney, D.J., (2001) J. Dental Res., 80, pp. 2025-9; Rowley, J.A., Madlambayan, G., Mooney, D.J., (1999) Biomaterials, 20, pp. 45-53; Hynes, R.O., (2002) Cell, 110, pp. 673-687; Qin, J., Vinogradova, O., Plow, E.F., (2004) PLoS Biol., 2, pp. e169; Medina-Kauwe, L.K., (2003) Adv. Drug Delivery Rev., 55, pp. 1485-1496; Stewart, P.L., Chiu, C.Y., Huang, S., Muir, T., Zhao, Y., Chait, B., Mathias, P., Nemerow, G.R., (1997) EMBO J., 16, pp. 1189-1198; Dufès, C., Uchegbu, I.F., Schätzlein, A.G., (2005) Adv. Drug Delivery Rev., 57, pp. 2177-2202; Mintzer, M.A., Simanek, E.E., (2009) Chem. Rev., 109, pp. 259-302; Smith, D.K., (2008) Curr. Top. Med. Chem., 8, pp. 1187-1203; Svenson, S., Tomalia, D.A., (2005) Adv. Drug Delivery Rev., 57, pp. 2106-2129; Dennig, J., Duncan, E., (2002) J. Biotechnol., 90, pp. 339-347; Sokolova, V.V., Radtke, I., Heumann, R., Epple, M., (2006) Biomaterials, 27, pp. 3147-3153; Kukowska-Latallo, J.F., Bielinska, A.U., Johnson, J., Spindler, R., Tomalia, D.A., Baker Jr., J.R., (1996) Proc. Natl. Acad. Sci. U.S.A., 93, pp. 4897-4902; Santos, J.L., Oramas, E., Pêgo, A.P., Granja, P.L., Tomás, H., (2009) J. Controlled Release, 134, pp. 141-148; Prockop, D.J., (2009) Mol. Ther., 17, pp. 939-946; Väänänen, H.K., (2005) Ann. Med., 37, pp. 469-479; Gronthos, S., Simmons, P.J., Graves, S.E., Robey, P.G., (2001) Bone, 28, pp. 174-181; Snyder, S.L., Sobocinski, P.Z., (1975) Anal. Biochem., 64, pp. 284-288; Haensler, J., Szoka Jr., F.C., (1993) Bioconjugate Chem, 4, pp. 372-379; Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., (1985) Anal. Biochem., 150, pp. 76-85; Perrot, S., Dutertre-Catella, H., Martin, C., Rat, P., Warnet, J.M., (2003) Toxicol. Sci., 72, pp. 122-129; Hosseinkhani, H., Yamamoto, M., Inatsugu, Y., Hiraoka, Y., Inoue, S., Shimokawa, H., Tabata, Y., (2006) Biomaterials, 27, pp. 1387-1398; Zhang, S., Li, J., Lykotrafitis, G., Bao, G., Suresh, S., (2009) Adv. Mater., 21, pp. 419-424; Tang, M.X., Szoka, F.C., (1997) Gene Ther., 4, pp. 823-32; Santos, J.L., Pandita, D., Rodrigues, J., Pêgo, A.P., Granja, P.L., Balian, G., Tomás, H., (2010) Mol. Pharm., 7, pp. 763-774; Santos, J.L., Oliveira, H., Pandita, D., Rodrigues, J., Pêgo, A.P., Granja, P.L., Tomás, H., (2010) J. Controlled Release, 144, pp. 55-64; Kunath, K., Merdan, T., Hegener, O., Häberlein, H., Kissel, T., (2003) J. Gene Med., 5, pp. 588-599; Lechardeur, D., Verkman, A.S., Lukacs, G.L., (2005) Adv. Drug Delivery Rev., 57, pp. 755-767; Ryoo, H.M., Lee, M.H., Kim, Y.J., (2006) Gene, 366, pp. 51-57
Keywords: Amino Acid Sequence; Amino acids; animal cell; animal experiment; Animals; Arginine-glycine-aspartic acids; arginylglycylaspartic acid; article; Biomimetics; bone morphogenetic protein 2; Bone morphogenetic protein-2; Cell culture; Cell membranes; cell surface; Cell surfaces; cell survival; Cellular response; Cluster formations; Complexation; controlled study; dendrimer; Dendrimers; Electrostatic interactions; electrostatic precipitation; Encoding (symbols); Enhanced green fluorescent protein; Firefly luciferase; Functional polymers; Gene delivery; Gene delivery vectors; gene expression; gene targeting; Gene therapy; Gene transfer; Gene Transfer Techniques; gene vector; integrin; Integrins; male; Mesenchymal stem cell; Mesenchymal Stem Cells; Molecular Structure; Nanoclusters; Nanostructures; New approaches; nonhuman; Oligopeptides; Organic acids; Peptides; plasmid DNA; Plasmid DNA (pDNA); polyamidoamine; Polyamidoamine dendrimers; Polyamines; priority journal; rat; Rats; Rats, Wistar; RGD motif; Scaffolds; Stem cells; Structure-Activity Relationship; Targeting capability; Transfection efficiency; Vectors; Zeta potential

New results on minimum error entropy decision trees - De Sá, J.P.M.; Sebastião, R.; Gama, J.; Fontes, T. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2011)
We present new results on the performance of Minimum Error Entropy (MEE) decision trees, which use a novel node split criterion. The results were obtained in a comparive study with popular alternative algorithms, on 42 real world datasets. Carefull validation and statistical methods were used. The evidence gathered from this body of results show that the error performance of MEE trees compares well with alternative algorithms. An important aspect to emphasize is that MEE trees generalize better on average without sacrifing error performance. © 2011 Springer-Verlag.
Conference code: 87418Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-25085-9_42Language of Original Document: EnglishCorrespondence Address: De Sá, J.P.M.; INEB-Instituto de Engenharia Biomédica, FEUP, Universidade Do Porto, Rua Dr. Roberto Frias, s/n, 4200-465 Porto, Portugal; email: jmsa@fe.up.ptReferences: Rokach, L., Maimon, O., Decision Trees (2005) Data Mining and Knowledge Discovery Handbook, , Maimon, O., Rokach, L. (eds.) Springer, Heidelberg;Marques De Sá, J.P., Sebastião, R., Gama, J., Tree Classifiers Based on Minimum Error Entropy Decisions (2011) Can. J. Artif. Intell., Patt. Rec. and Mach. Learning, , in press; Silva, L., Felgueiras, C.S., Alexandre, L., Marques De Sá, J., Error Entropy in Classification Problems: A Univariate Data Analysis (2006) Neural Computation, 18, pp. 2036-2061; Asuncion, A., Newman, D.J., (2010) UCI Machine Learning Repository, , http://www.ics.uci.edu/~mlearn/MLRepository.html; Kearns, M., A Bound on the Error of Cross Validation Using the Approximation and Estimation Rates, with Consequences for the Training-Test Split (1997) Neural Computation, 9, pp. 1143-1161; Molinaro, A.M., Simon, R., Pfeiffer, R.M., Prediction Error Estimation: A Comparison of Resampling Methods (2005) Bioinformatics, 21, pp. 3301-3307; Demšar, J., Statistical Comparisons of Classifiers over Multiple Data Sets (2006) J. of Machine Learning Research, 7, pp. 1-30; García, S., Fernández, A., Luengo, J., Herrera, F., Advanced Nonparametric Tests for Multiple Comparisons in the Design of Experiments in Computational Intelligence and Data Mining: Experimental Analysis of Power (2010) Information Sciences, 180, pp. 2044-2064; Hochberg, Y., Tamhane, A.C., (1987) Multiple Comparison Procedures, , John Wiley & Sons, Inc; Salzberg, S.L., On Comparing Classifiers: Pitfalls to Avoid and a Recommended Approach (1997) Data Mining and Knowledge Discovery, 1, pp. 317-328; Jensen, D., Oates, T., Cohen, P.R., Building Simple Models: A Case Study with Decision Trees (1997) LECTURE NOTES IN COMPUTER SCIENCE, (1280), pp. 211-222. , Advances in Intelligent Data Analysis Reasoning about Data; Li, R.-H., Belford, G.G., Instability of Decision Tree Classification Algorithms (2002) Proc. 8th ACM SIGKDD International Conference on Knowledge Discovery and Data Mining, pp. 570-575 Sponsors: Universidad de La Frontera (UFRO); The International Association for Pattern Recognition (IAPR); Asociacon Chilena de Reconocimiento de Patrones (AChiRP); Asociacion Cubana de Reconocimiento de Patrones (ACPR); Mex. Assoc. Comput. Vis., Neural Comput. Rob. (MACVNR)
Keywords: Algorithms; Alternative algorithms; Computer vision; Decision Theory; decision trees; entropy; entropy-of-error; Error entropy; Error performance; Forestry; New results; node split criteria; Real-world datasets; Vision

Non-viral gene delivery to mesenchymal stem cells: Methods, strategies and application in bone tissue engineering and regeneration - Santos, J.L.; Pandita, D.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (Current Gene TherapyCurr. Gene Ther., 2011)
Mesenchymal stem cells (MSCs) can be isolated from several tissues in the body, have the ability to selfrenewal, show immune suppressive properties and are multipotent, being able to generate various cell types. At present, due to their intrinsic characteristics, MSCs are considered very promising in the area of tissue engineering and regenerative medicine. In this context, genetic modification can be a powerful tool to control the behavior and fate of these cells and be used in the design of new cellular therapies. Viral systems are very effective in the introduction of exogenous genes inside MSCs. However, the risks associated with their use are leading to an increasing search for non-viral approaches to attain the same purpose, even if MSCs have been shown to be more difficult to transfect in this way. In the past few years, progress was made in the development of chemical and physical methods for non-viral gene delivery. Herein, an overview of the application of those methods specifically to MSCs is given and their use in tissue engineering and regenerative medicine therapeutic strategies highlighted using the example of bone tissue. Key issues and future directions in non-viral gene delivery to MSCs are also critically addressed. © 2011 Bentham Science Publishers Ltd.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: CGTUAdoi: 10.2174/156652311794520102PubMed ID: 21182464Language of Original Document: EnglishCorrespondence Address: Tomás, H.; CQM-Centro de Química da Madeira, MMRG, Universidade da Madeira, Campus Universitário da Penteada, 9000-390 Funchal, Portugal; email: lenat@uma.ptReferences: Bianco, P., Robey, P.G., Simmons, P.J., Mesenchymal stem cells: Revisitinghistory, concepts, and assays (2008) Cell Stem Cell, 2, pp. 313-319;Marot, D., Knezevic, M., Novakovic, G.V., Bone tissue engineeringwith human stem cells (2010) Stem Cell Res Ther, 1, p. 10; Caplan, A.I., Review: Mesenchymal stem cells: Cell-based reconstructivetherapy in orthopedics (2005) Tissue Eng, 11, pp. 1198-1211; Caplan, A.I., Bruder, S.P., Mesenchymal stem cells: Building blocksfor molecular medicine in the 21st century (2001) Trends Mol Med, 7, pp. 259-264; Chen, F.H., Tuan, R.S., Mesenchymal stem cells in arthritic diseases (2008) Arthritis Res Ther, 10, p. 223; Da Silva Meirelles, L., Chagastelles, P.C., Nardi, N.B., Mesenchymalstem cells reside in virtually all post-natal organs and tissues (2006) J CellSci, 119, pp. 2204-2213; Mauney, J.R., Volloch, V., Kaplan, D.L., Role of adult mesenchymalstem cells in bone tissue engineering applications: Current statusand future prospects (2005) Tissue Eng, 11, pp. 787-802; Prockop, D.J., Repair of tissues by adult stem/progenitor cells(MSCs): Controversies, myths, and changing paradigms (2009) Mol Ther, 17, pp. 939-946; Sakurada, K., McDonald, F.M., Shimada, F., Regenerative medicineand stem cell based drug discovery (2008) Angew Chem Int Ed Engl, 47, pp. 5718-5738; Väänänen, H.K., Mesenchymal stem cells (2005) Ann Med, 37, pp. 469-479; Jackson, W.M., Nesti, L.J., Tuan, R.S., Potential therapeutic applicationsof muscle-derived mesenchymal stem and progenitor cells (2010) ExpertOpin Biol Ther, 10, pp. 505-517; Nauta, A.J., Fibbe, W.E., Immunomodulatory properties of mesenchymalstromal cells (2007) Blood, 110, pp. 3499-3506; Heyde, M., Partridge, K.A., Oreffo, R.O., Gene therapy used fortissue engineering applications (2007) J Pharm Pharmacol, 59, pp. 329-350; Kimelman, N., Pelled, G., Helm, G.A., Review: Gene-and stemcell-based therapeutics for bone regeneration and repair (2007) TissueEng, 13, pp. 1135-1150; Partridge, K.A., Oreffo, R.O., Gene delivery in bone tissue engineering: Progress and prospects using viral and nonviral strategies (2004) TissueEng, 10, pp. 295-307; Pittenger, M., Vanguri, P., Simonetti, D., Adult mesenchymalstem cells: Potential for muscle and tendon regeneration and use ingene therapy (2002) J Musculoskelet Neuronal Interact, 2, pp. 309-320; Reiser, J., Zhang, X.Y., Hemenway, C.S., Potential of mesenchymalstem cells in gene therapy approaches for inherited and acquireddiseases (2005) Expert Opin Biol Ther, 5, pp. 1571-1584; Saraf, A., Mikos, A.G., Gene delivery strategies for cartilage tissueengineering (2006) Adv Drug Deliv Rev, 58, pp. 592-603; Trippel, S.B., Ghivizzani, S.C., Nixon, A.J., Gene-based approaches forthe repair of articular cartilage (2004) Gene Ther, 11, pp. 351-359; Takahashi, K., Yamanaka, S., Induction of pluripotent stem cells frommouse embryonic and adult fibroblast cultures by defined factors (2006) Cell, 126, pp. 663-676; Yu, J., Vodyanik, M.A., Smuga-Otto, K., Induced pluripotentstem cell lines derived from human somatic cells (2007) Science, 318, pp. 1917-1920; Steinert, A.F., Noth, U., Tuan, R.S., Concepts in gene therapy for cartilagerepair (2008) Injury, 39 (SUPPL 1), pp. S97-S113; Gafni, Y., Turgeman, G., Liebergal, M., Stem cells as vehiclesfor orthopedic gene therapy (2004) Gene Ther, 11, pp. 417-426; Kane, N.M., McRae, S., Denning, C., Viral and non-viral genedelivery and its role in pluripotent stem cell engineering Drug DiscovToday: Technol, , In press. doi:10.1016/j.ddtec.2008.10.002; Li, S.D., Huang, L., Non-viral is superior to viral gene delivery (2007) JControl Release, 123, pp. 181-183; Mastrobattista, E., Bravo, S.A., van der Aa, M., Nonviral genedelivery systems: From simple transfection agents to artificial viruses (2005) Drug Discov Today: Technol, 2, pp. 103-109; Chan, J., O'Donoghue, K., de la Fuente, J., Human fetal mesenchymalstem cells as vehicles for gene delivery (2005) Stem Cells, 23, pp. 93-102; Tsuda, H., Wada, T., Yamashita, T., Enhanced osteoinduction bymesenchymal stem cells transfected with a fiber-mutant adenoviralBMP2 gene (2005) J Gene Med, 7, pp. 1322-1334; Zhang, X., Godbey, W.T., Viral vectors for gene delivery in tissueengineering (2006) Adv Drug Deliv Rev, 58, pp. 515-534; Dang, J.M., Leong, K.W., Natural polymers for gene delivery and tissue engineering (2006) Adv Drug Deliv Rev, 58, pp. 487-499; Luten, J., van Nostrum, C.F., De Smedt, S.C., Biodegradablepolymers as non-viral carriers for plasmid DNA delivery (2008) J ControlRelease, 126, pp. 97-110; Mintzer, M.A., Simanek, E.E., Nonviral vectors for gene delivery (2009) Chem Rev, 109, pp. 259-302; Panyam, J., Labhasetwar, V., Biodegradable nanoparticles for drugand gene delivery to cells and tissue (2003) Adv Drug Deliv Rev, 55, pp. 329-347; Choi, J.S., Ko, K.S., Park, J.S., Dexamethasone conjugatedpoly(amidoamine) dendrimer as a gene carrier for efficient nucleartranslocation (2006) Int J Pharm, 320, pp. 171-178; Roth, C.M., Sundaram, S., Engineering synthetic vectors for improvedDNA delivery: Insights from intracellular pathways (2004) Annu RevBiomed Eng, 6, pp. 397-426; Wood, K.C., Little, S.R., Langer, R., A family of hierarchicallyself-assembling linear-dendritic hybrid polymers for highly efficienttargeted gene delivery (2005) Angew Chem Int Ed Engl, 44, pp. 6704-6708; Mehier-Humbert, S., Guy, R.H., Physical methods for gene transfer: Improving the kinetics of gene delivery into cells (2005) Adv Drug DelivRev, 57, pp. 733-753; Jo, J., Tabata, Y., Non-viral gene transfection technologies for geneticengineering of stem cells (2008) Eur J Pharm Biopharm, 68, pp. 90-104; Song, L., Chau, L., Sakamoto, Y., Electric field-induced molecularvibration for noninvasive, high-efficiency DNA transfection (2004) Mol Ther, 9, pp. 607-616; Han, S.W., Nakamura, C., Kotobuki, N., High-efficiency DNAinjection into a single human mesenchymal stem cell using ananoneedle and atomic force microscopy (2008) Nanomedicine, 4, pp. 215-225; Park, S., Kim, Y.S., Kim, W.B., Carbon nanosyringe array as aplatform for intracellular delivery (2009) Nano Lett, 9, pp. 1325-1329; Durieux, A.C., Bonnefoy, R., Busso, T., In vivo gene electrotransferinto skeletal muscle: Effects of plasmid DNA on the occurrenceand extent of muscle damage (2004) J Gene Med, 6, pp. 809-816; Winn, S.R., Hu, Y., Sfeir, C., Gene therapy approaches for modulatingbone regeneration (2000) Adv Drug Deliv Rev, 42, pp. 121-138; Lv, H., Zhang, S., Wang, B., Toxicity of cationic lipids and cationicpolymers in gene delivery (2006) J Control Release, 114, pp. 100-109; Gebhart, C.L., Kabanov, A.V., Evaluation of polyplexes as gene transferagents (2001) J Control Release, 73, pp. 401-416; Hamm, A., Krott, N., Breibach, I., Efficient transfection methodfor primary cells (2002) Tissue Eng, 8, pp. 235-245; Gill, D.R., Pringle, I.A., Hyde, S.C., Progress and prospects: The designand production of plasmid vectors (2009) Gene Ther, 16, pp. 165-171; Miller, A.M., Dean, D.A., Tissue-specific and transcription factormediatednuclear entry of DNA (2009) Adv Drug Deliv Rev, 61, pp. 603-613; Smith, D.K., Dendrimers and the double helix--from DNA bindingtowards gene therapy (2008) Curr Top Med Chem, 8, pp. 1187-1203; Duzgunes, N., De Ilarduya, C.T., Simoes, S., Cationic liposomesfor gene delivery: Novel cationic lipids and enhancement by proteinsand peptides (2003) Curr Med Chem, 10, pp. 1213-1220; Hoekstra, D., Rejman, J., Wasungu, L., Gene delivery by cationiclipids: In and out of an endosome (2007) Biochem Soc Trans, 35, pp. 68-71; Hoelters, J., Ciccarella, M., Drechsel, M., Nonviral genetic modificationmediates effective transgene expression and functionalRNA interference in human mesenchymal stem cells (2005) J Gene Med, 7, pp. 718-728; Ko, B.S., Chang, T.C., Shyue, S.K., An efficient transfectionmethod for mouse embryonic stem cells (2009) Gene Ther, 16, pp. 154-158; Park, J., Lutz, R., Felszeghy, E., The effect on bone regenerationof a liposomal vector to deliver BMP-2 gene to bone grafts in periimplantbone defects (2007) Biomaterials, 28, pp. 2772-2782; Park, J., Ries, J., Gelse, K., Bone regeneration in critical sizedefects by cell-mediated BMP-2 gene transfer: A comparison of adenoviral vectors and liposomes (2003) Gene Ther, 10, pp. 1089-1098; Vanderbyl, S., McDonald, G.N., Sidhu, S., Transfer and stabletransgene expression of a mammalian artificial chromosome intobone marrow-derived human mesenchymal stem cells (2004) Stem Cells, 22, pp. 324-333; de Jong, G., Telenius, A., Vanderbyl, S., Efficient in-vitro transferof a 60-Mb mammalian artificial chromosome into murine and hamster cells using cationic lipids and dendrimers (2001) ChromosomeRes, 9, pp. 475-485; Dass, C.R., Cytotoxicity issues pertinent to lipoplex-mediated genetherapy in-vivo (2002) J Pharm Pharmacol, 54, pp. 593-601; Wu, G.Y.W.C., Receptor-mediated in vitro gene transformation by asoluble DNA carrier system (1987) J Biol Chem, 262, pp. 4429-4432; Choi, Y.H., Liu, F., Kim, J.S., Polyethylene glycol-grafted poly-Llysineas polymeric gene carrier (1998) J Control Release, 54, pp. 39-48; Liu, G., Molas, M., Grossmann, G.A., Biological properties of poly-L-lysine-DNA complexes generated by cooperative binding of the polycation (2001) J Biol Chem, 276, pp. 34379-34387; Farrell, L.L., Pepin, J., Kucharski, C., A comparison of the effectivenessof cationic polymers poly-L-lysine (PLL) and polyethylenimine(PEI) for non-viral delivery of plasmid DNA to bone marrowstromal cells (BMSC) (2007) Eur J Pharm Biopharm, 65, pp. 388-397; Incani, V., Tunis, E., Clements, B.A., Palmitic acid substitutionon cationic polymers for effective delivery of plasmid DNA tobone marrow stromal cells (2007) J Biomed Mater Res A, 81, pp. 493-504; Clements, B.A., Incani, V., Kucharski, C., A comparative evaluationof poly-L-lysine-palmitic acid and Lipofectamine 2000 forplasmid delivery to bone marrow stromal cells (2007) Biomaterials, 28, pp. 4693-4704; Bragonzi, A., Boletta, A., Biffi, A., Comparison between cationicpolymers and lipids in mediating systemic gene delivery to thelungs (1999) Gene Ther, 6, pp. 1995-2004; Sea, F., Exgen 500 is an efficient vector for gene delivery tolung epithelial cells in vitro and in vivo (1997) Gene Ther, 4, pp. 1100-1106; Wightman, L., Kircheis, R., Rossler, V., Different behavior of branched and linear polyethylenimine for gene delivery in vitro and in vivo (2001) J Gene Med, 3, pp. 362-372; Behr, J.-P., The Proton Sponge: A Trick to Enter Cells the VirusesDid Not Exploit (1997) Chimia, 51, pp. 34-36; Dea, F., A novel non-viral vector for DNA delivery based onlow molecular weight, branched polyethylenimine: Effect of molecularweight on transfection efficiency and cytotoxicity (1999) Pharm. Res, 16, pp. 1273-1279; Godbey, W.T., Wu, K.K., Mikos, A.G., Size matters: Molecular weightaffects the efficiency of poly(ethylenimine) as a gene delivery vehicle (1999) J Biomed Mater Res, 45, pp. 268-275; Ahn, H.H., Lee, M.S., Cho, M.H., DNA/PEI nano-particles forgene delivery of rat bone marrow stem cells (2008) Colloids and SurfacesA: Physicochem Eng Aspects, 313-314, pp. 116-120; Ahn, H.H., Lee, J.H., Kim, K.S., Polyethyleneimine-mediated genedelivery into human adipose derived stem cells (2008) Biomater, 29, pp. 2415-2422; Clements, B.A., Bai, J., Kucharski, C., RGD conjugation to polyethyleneiminedoes not improve DNA delivery to bone marrowstromal cells (2006) Biomacromolecules, 7, pp. 1481-1488; Saraf, A., Hacker, M.C., Sitharaman, B., Synthesis and conformationalevaluation of a novel gene delivery vector for human mesenchymalstem cells (2008) Biomacromolecules, 9, pp. 818-827; Lei, Y., Segura, T., DNA delivery from matrix metalloproteinasedegradable poly(ethylene glycol) hydrogels to mouse cloned mesenchymalstem cells (2009) Biomaterials, 30, pp. 254-265; Gwak, S.J., Kim, B.S., Poly(lactic-co-glycolic acid) nanosphere as avehicle for gene delivery to human cord blood-derived mesenchymalstem cells: Comparison with polyethylenimine (2008) Biotechnol Lett, 30, pp. 1177-1182; Yang, F., Green, J.J., Dinio, T., Gene delivery to human adult and embryonic cell-derived stem cells using biodegradable nanoparticulatepolymeric vectors (2009) Gene Ther, 16, pp. 533-546; Huang, M., Fong, C.W., Khor, E., Transfection efficiency of chitosan vectors: Effect of polymer molecular weight and degree of deacetylation (2005) J Control Release, 106, pp. 391-406; Ishii, T., Okahata, Y., Sato, T., Mechanism of cell transfection withplasmid/chitosan complexes (2001) Biochim Biophys Acta, 1514, pp. 51-64; Moreira, C., Oliveira, H., Pires, L.R., Improving chitosanmediatedgene transfer by the introduction of intracellular bufferingmoieties into the chitosan backbone (2009) Acta Biomater, 5, pp. 2995-3006; Sato, T., Ishii, T., Okahata, Y., In vitro gene delivery mediated bychitosan. effect of pH, serum, and molecular mass of chitosan onthe transfection efficiency (2001) Biomaterials, 22, pp. 2075-2080; Corsi, K., Chellat, F., Yahia, L., Mesenchymal stem cells, MG63and HEK293 transfection using chitosan-DNA nanoparticles (2003) Biomaterials, 24, pp. 1255-1264; Nie, H., Wang, C.H., Fabrication and characterization of PLGA/HApcomposite scaffolds for delivery of BMP-2 plasmid DNA (2007) J ControlRelease, 120, pp. 111-121; Hu, Y., Cai, K., Luo, Z., Surface mediated in situ differentiationof mesenchymal stem cells on gene-functionalized titanium filmsfabricated by layer-by-layer technique (2009) Biomaterials, 30, pp. 3626-3635; Okazaki, A., Jo, J., Tabata, Y., A reverse transfection technology togenetically engineer adult stem cells (2007) Tissue Eng, 13, pp. 245-251; Hosseinkhani, H., Azzam, T., Kobayashi, H., Combination of 3Dtissue engineered scaffold and non-viral gene carrier enhance in vitroDNA expression of mesenchymal stem cells (2006) Biomaterials, 27, pp. 4269-4278; Hosseinkhani, H., Yamamoto, M., Inatsugu, Y., Enhanced ectopicbone formation using a combination of plasmid DNA impregnationinto 3-D scaffold and bioreactor perfusion culture (2006) Biomaterials, 27, pp. 1387-1398; Dufès, C., Uchegbu, I.F., Schätzlein, A.G., Dendrimers in gene delivery (2005) Adv Drug Deliv Rev, 57, pp. 2177-2202; Svenson, S., Tomalia, D.A., Dendrimers in biomedical applications--reflections on the field (2005) Adv Drug Deliv Rev, 57, pp. 2106-2129; Malik, N., Wiwattanapatapee, R., Klopsch, R., Dendrimers: Relationshipbetween structure and biocompatibility in vitro, and preliminarystudies on the biodistribution of 125I-labelled polyamidoaminedendrimers in vivo (2000) J Control Release, 65, pp. 133-148; Duncan, R., Izzo, L., Dendrimer biocompatibility and toxicity (2005) AdvDrug Deliv Rev, 57, pp. 2215-2237; Dennig, J., Duncan, E., Gene transfer into eukaryotic cells usingactivated polyamidoamine dendrimers (2002) J Biotechnol, 90, pp. 339-347; Sokolova, V.V., Radtke, I., Heumann, R., Effective transfection of cells with multi-shell calcium phosphate-DNA nanoparticles (2006) Biomaterials, 27, pp. 3147-3153; Santos, J.L., Oramas, E., Pego, A.P., Osteogenic differentiation of mesenchymal stem cells using PAMAM dendrimers as gene deliveryvectors (2009) J Control Release, 134, pp. 141-148; Gheisari, Y., Soleimani, M., Azadmanesh, K., Multipotent mesenchymalstromal cells: Optimization and comparison of five cationicpolymer-based gene delivery methods (2008) Cytotherapy, 10, pp. 815-823; Holladay, C., Keeney, M., Greiser, U., A matrix reservoir forimproved control of non-viral gene delivery (2009) J Control Release, 136, pp. 220-225; Parekh, H.S., The advance of dendrimers-a versatile targeting platformfor gene/drug delivery (2007) Curr Pharm Des, 13, pp. 2837-2850; Santos, J.L., Pandita, D., Rodrigues, J., Receptor-mediated genedelivery using PAMAM dendrimers conjudated with peptides recognizedby mesenchymal stem cells (2010) Mol Pharmaceutics, 7, pp. 763-774; Santos, J.L., Oliveira, H., Pandita, D., Rodrigues, J., Functionalizationof Poly(amidoamine) Dendrimers with hydrophobic chains forimproved gene delivery in mesenchymal stem cells (2010) J Control Release, 144, pp. 55-64; Bourgeat-Lami, E., Organic-inorganic nanostructured colloids (2002) JNanosci Nanotechnol, 2, pp. 1-24; Chowdhury, E.H., Akaike, T., Bio-functional inorganic materials: Anattractive branch of gene-based nano-medicine delivery for 21stcentury (2005) Curr Gene Ther, 5, pp. 669-676; Sokolova, V., Epple, M., Inorganic nanoparticles as carriers of nucleicacids into cells (2008) Angew Chem Int Ed Engl, 47, pp. 1382-1395; Uchimura, E., Yamada, S., Uebersax, L., Method for reversetransfection using gold colloid as a nano-scaffold (2007) J Biosci Bioeng, 103, pp. 101-103; Gonzalez-McQuire, R., Green, D.W., Partridge, K.A., Coating of human mesenchymal cells in 3D culture with bioinorganicnanoparticles promotes osteoblastic differentiation and gene transfection (2007) Adv Mater, 19, pp. 2236-2240; Park, J.S., Na, K., Woo, D.G., Non-viral gene delivery of DNApolyplexed with nanoparticles transfected into human mesenchymalstem cells (2010) Biomaterials, 31, pp. 124-132; Peister, A., Mellad, J.A., Wang, M., Stable transfection of MSCsby electroporation (2004) Gene Ther, 11, pp. 224-228; Ferreira, E., Potier, E., Logeart-Avramoglou, D., Optimization of a gene electrotransfer method for mesenchymal stem cell transfection (2008) Gene Ther, 15, pp. 537-544; Ziv, R., Steinhardt, Y., Pelled, G., Micro-electroporation of mesenchymalstem cells with alternating electrical current pulses (2009) BiomedMicrodevices, 11, pp. 95-101; Lim, J.Y., Park, S.H., Jeong, C.H., Microporation is a valuabletransfection method for efficient gene delivery into human umbilicalcord blood-derived mesenchymal stem cells (2010) BMC Biotechnol, 10, p. 38; Lee, S.-J., Kang, S.-W., Do, H.-J., Enhancement of bone regenerationby gene delivery of BMP2/Runx2 bicistronic vector into adipose-derived stromal cells (2010) Biomater, 31, pp. 5652-5659; Lakshmipathy, U., Pelacho, B., Sudo, K., Efficient transfection of embryonic and adult stem cells (2004) Stem Cells, 22, pp. 531-543; Aluigi, M., Fogli, M., Curti, A., Nucleofection is an efficientnonviral transfection technique for human bone marrow-derivedmesenchymal stem cells (2006) Stem Cells, 24, pp. 454-461; Nakashima, S., Matsuyama, Y., Nitta, A., Highly efficient transfectionof human marrow stromal cells by nucleofection (2005) TransplantProc, 37, pp. 2290-2292; Miller, D.L., Pislaru, S.V., Greenleaf, J.E., Sonoporation: MechanicalDNA delivery by ultrasonic cavitation (2002) Somat Cell Mol Genet, 27, pp. 115-134; Otani, K., Yamahara, K., Ohnishi, S., Nonviral delivery of siRNA into mesenchymal stem cells by a combination of ultrasoundand microbubbles (2009) J Control Release, 133, pp. 146-153; Aslan, H., Sheyn, D., Gazit, D., Genetically engineered mesenchymalstem cells: Applications in spine therapy (2009) Regen Med, 4, pp. 99-108; Chiang, G.G., Rubin, H.L., Cherington, V., Bone marrow stromalcell-mediated gene therapy for hemophilia A: In vitro expression of human factor VIII with high biological activity requires the inclusionof the proteolytic site at amino acid 1648 (1999) Hum Gene Ther, 10, pp. 61-76; Gelse, K., von der Mark, K., Schneider, H., Cartilage regeneration bygene therapy (2003) Curr Gene Ther, 3, pp. 305-317; Moutsatsos, I.K., Turgeman, G., Zhou, S., Exogenously regulatedstem cell-mediated gene therapy for bone regeneration (2001) Mol Ther, 3, pp. 449-461; Phillips, M.I., Tang, Y.L., Genetic modification of stem cells for transplantation (2008) Adv Drug Deliv Rev, 60, pp. 160-172; Schwarz, E.J., Reger, R.L., Alexander, G.M., Rat marrow stromalcells rapidly transduced with a self-inactivating retrovirus synthesizeL-DOPA in vitro (2001) Gene Ther, 8, pp. 1214-1223; Sun, M., Kong, L., Wang, X., Coexpression of tyrosine hydroxylase, GTP cyclohydrolase I, aromatic amino acid decarboxylase, and vesicular monoamine transporter 2 from a helper virus-freeherpes simplex virus type 1 vector supports high-level, long-termbiochemical and behavioral correction of a rat model of Parkinson'sdisease (2004) Hum Gene Ther, 15, pp. 1177-1196; Turgeman, G., Pittman, D.D., Muller, R., Engineered humanmesenchymal stem cells: A novel platform for skeletal cell mediatedgene therapy (2001) J Gene Med, 3, pp. 240-251; Tuszynski, M.H., Thal, L., Pay, M., A phase 1 clinical trial of nerve growth factor gene therapy for Alzheimer disease (2005) Nat Med, 11, pp. 551-555; Fang, J., Zhu, Y.Y., Smiley, E., Stimulation of new bone formationby direct transfer of osteogenic plasmid genes (1996) Proc Natl AcadSci U S A, 93, pp. 5753-5758; Bonadio, J., Smiley, E., Patil, P., Localized, direct plasmid genedelivery in vivo: Prolonged therapy results in reproducible tissueregeneration (1999) Nat Med, 5, pp. 753-759; Kasper, F.K., Young, S., Tanahashi, K., Evaluation of bone regenerationby DNA release from composites of oligo(poly(ethyleneglycol) fumarate) and cationized gelatin microspheres in a criticalsizedcalvarial defect (2006) J Biomed Mater Res A, 78, pp. 335-342; Kuroda, S., Kondo, H., Ohya, K., A new technique with calciumphosphate precipitate enhances efficiency of in vivo plasmid DNAgene transfer (2005) J Pharmacol Sci, 97, pp. 227-233; Endo, M., Kuroda, S., Kondo, H., Bone regeneration by modifiedgene-activated matrix: Effectiveness in segmental tibial defects inrats (2006) Tissue Eng, 12, pp. 489-497; Huang, Y.C., Simmons, C., Kaigler, D., Bone regeneration in a ratcranial defect with delivery of PEI-condensed plasmid DNA encodingfor bone morphogenetic protein-4 (BMP-4) (2005) Gene Ther, 12, pp. 418-426; Nie, H., Ho, M.L., Wang, C.K., BMP-2 plasmid loadedPLGA/HAp composite scaffolds for treatment of bone defects innude mice (2009) Biomaterials, 30, pp. 892-901; Ono, I., Yamashita, T., Jin, H.Y., Combination of porous hydroxyapatiteand cationic liposomes as a vector for BMP-2 genetherapy (2004) Biomaterials, 25, pp. 4709-4718; Kishimoto, K.N., Watanabe, Y., Nakamura, H., Ectopic boneformation by electroporatic transfer of bone morphogenetic protein-4 gene (2002) Bone, 31, pp. 340-347; Sheyn, D., Kimelman-Bleich, N., Pelled, G., Ultrasound-basednonviral gene delivery induces bone formation in vivo (2008) Gene Ther, 15, pp. 257-266; Hosseinkhani, H., Inatsugu, Y., Hiraoka, Y., Impregnation of plasmid DNA into three-dimensional scaffolds and medium perfusionenhance in vitro DNA expression of mesenchymal stem cells (2005) Tissue Eng, 11, pp. 1459-1475; Hosseinkhani, H., Hosseinkhani, M., Gabrielson, N.P., DNAnanoparticles encapsulated in 3D tissue-engineered scaffolds enhanceosteogenic differentiation of mesenchymal stem cells (2007) JBiomed Mater Res A, 85, pp. 47-60; Huang, Y.C., Kaigler, D., Rice, K.G., Combined angiogenic and osteogenic factor delivery enhances bone marrow stromal celldrivenbone regeneration (2005) J Bone Miner Res, 20, pp. 848-857; Blum, J.S., Barry, M.A., Mikos, A.G., In vivo evaluation of genetherapy vectors in ex vivo-derived marrow stromal cells for boneregeneration in a rat critical-size calvarial defect model (2003) Hum GeneTher, 14, pp. 1689-1701; Aslan, H., Zilberman, Y., Arbeli, V., Nucleofection-based ex vivononviral gene delivery to human stem cells as a platform for tissueregeneration (2006) Tissue Eng, 12, pp. 877-889; Noel, D., Gazit, D., Bouquet, C., Short-term BMP-2 expression issufficient for in vivo osteochondral differentiation of mesenchymalstem cells (2004) Stem Cells, 22, pp. 74-85
Keywords: Animals; article; artificial chromosome; Bone and Bones; Bone Regeneration; bone tissue; Bone tissue engineering; cell based gene therapy; dendrimer; ex vivo gene transfer; Gene delivery; gene targeting; Gene therapy; Gene Transfer Techniques; gene vector; genetic transfection; human; Humans; in vivo gene transfer; liposome; Mesenchymal stem cell; Mesenchymal Stem Cells; nanomedicine; nanoparticle; Non-viral vectors; nonhuman; nonviral gene delivery system; polymer; protein expression; Regeneration; Regenerative Medicine; Tissue engineering; Tissue regeneration

Scientists perception of ethical issues in nanomedicine: A case study - Silva Costa, H.; Sethe, S.; Pêgo, A.P.; Olsson, I.A.S. (NanomedicineNanomedicine, 2011)
Aim: Research and development in nanomedicine has been accompanied by the consideration of ethical issues; however, little is known about how researchers working in this area perceive such issues. This case-study explores scientists attitude towards and knowledge of ethical issues. Method: Data were collected by semi-structured interviews with 22 nanomedicine practitioners and subject to content analysis. Results: We found that scientists reflect with ambiguity on the reputed novelty of nanomedicine and what the ethical issues and risks are in their work. Respondents see no necessity for a paradigm shift in ethical considerations, but view ethical issues in nanomedicine as overlapping with those of other areas of biomedical research. Most respondents discuss ethical issues they faced in scientific work with their colleagues, but expect benefit from additional information and training on ethics. Conclusion: Our findings that scientists are motivated to reflect on ethical issues in their work, can contribute to the design of new strategies, including training programs, to engage scientists in ethical discussion and stimulate their responsibility as nanomedicine practitioners. © 2011 Future Medicine Ltd.
Keywords: adult; ambiguity; article; attitude; case study; clinical article; empirical research; ethics; Female; human; Humans; information; knowledge; male; medical ethics; medical research; Middle Aged; Models, Theoretical; nanomedicine; Nanotechnology; perception; priority journal; professional practice; qualitative study; Research Personnel; responsibility; risks; scientist; scientists perception; semi structured interview; training; Young Adult

Segmentation of ultrasound images of the carotid using RANSAC and cubic splines - Rocha, R.; Campilho, A.; Silva, J.; Azevedo, E.; Santos, R. (Computer Methods and Programs in BiomedicineComput. Methods Programs Biomed., 2011)
A new algorithm is proposed for the semi-automatic segmentation of the near-end and the far-end adventitia boundary of the common carotid artery in ultrasound images. It uses the random sample consensus method to estimate the most significant cubic splines fitting the edge map of a longitudinal section. The consensus of the geometric model (a spline) is evaluated through a new gain function, which integrates the responses to different discriminating features of the carotid boundary: the proximity of the geometric model to any edge or to valley shaped edges; the consistency between the orientation of the normal to the geometric model and the intensity gradient; and the distance to a rough estimate of the lumen boundary.A set of 50 longitudinal B-mode images of the common carotid and their manual segmentations performed by two medical experts were used to assess the performance of the method. The image set was taken from 25 different subjects, most of them having plaques of different classes (class II to class IV), sizes and shapes.The quantitative evaluation showed promising results, having detection errors similar to the ones observed in manual segmentations for 95% of the far-end boundaries and 73% of the near-end boundaries. © 2011 Elsevier Ireland Ltd.
Cited By (since 1996): 10Export Date: 21 November 2012Source: ScopusCODEN: CMPBEdoi: 10.1016/j.cmpb.2010.04.015PubMed ID: 20554343Language of Original Document: EnglishCorrespondence Address: Rocha, R.; INEB, Divisão de Sinal e Imagem, Campus FEUP, 4200-465 Porto, Portugal; email: rhr@isep.ipp.ptReferences: Baldassarre, D., Amato, M., Bondioli, A., Sirtori, C.R., Tremoli, E., Carotid artery intima-media thickness measured by ultrasonography in normal clinical practice correlates well with atherosclerosis risk factors (2000) Stroke, 31, pp. 2426-2430;O'Leary, D., Polak, J., Kronmal, R., Manolio, T., Burke, G.W.S., Carotid-artery intima and media thickness as a risk factor for myocardial infarction and stroke in older adults (1999) N. Engl. J. Med., 340, pp. 14-22; Hodis, H., Mack, W., LaBree, L., Selzer, R., Liu, C., Liu, C., Azen, S., The role of carotid arterial intima-media thickness in predicting clinical coronary events (1998) Ann. Intern. Med., 128 (4), pp. 262-269; Reneman, R.S., Meinders, J.M., Hoeks, A.P.G., Non-invasive ultrasound in arterial wall dynamics in humans: what have we learned and what remains to be solved (2005) Eur. Heart J., 26, pp. 960-966; Gee, A., Prager, R., Treece, G., Berman, L., Engineering a freehand 3D ultrasound system (2003) Pattern Recogn. Lett., 24 (4-5), pp. 757-777; Sonka, M., Liang, W., Stefancik, R., Stolpen, A., (2000), 2. , Handbook of Medical Imaging: Medical Image Processing and Analysis,SPIEGiannoglou, G.D., Chatzizisis, Y.S., Koutkias, V., Kompatsiaris, I., Papadogiorgaki, M., Mezaris, V., Parissi, E., Louridas, G.E., A novel active contour model for fully automated segmentation of intravascular ultrasound images: in vivo validation in human coronary arteries (2008) Comput. Biol. Med., 37 (9), pp. 1292-1302; Tsai, A., Yezzi, A.J., Tempany, C., Tucker, D., Fan, A., Grimson, W.E.L., Willsky, A.S., A shape-based approach to the segmentation of medical imagery using level sets (2003) IEEE Trans. Med. Imaging, 22 (2), pp. 137-154; Cremers, D., Kohlberger, T., Schnorr, C., Nonlinear shape statistics in Mumford-Shah based segmentation (2002) Proc. European Conf. on Computer Vision (ECCV'2002), vol. 2351, pp. 93-108; Cremers, D., Sochen, N., Schnorr, C., Towards recognition-based variational segmentation using shape priors and dynamic labeling (2003) Proc. European Conf. on Computer Vision (ECCV'2003), vol. 2695, pp. 388-400; Cremers, D., Osher, S., Soatto, S., Kernel density estimation and intrinsic alignment for knowledge-driven segmentation: teaching level sets to walk (2004) Pattern Recognit., 3175, pp. 36-44; Halenka, M., Noninvasive measurement of early atherosclerosis by high-resolution B-mode ultrasonography (1999) Acta-Universitatis Palackianae Olomucensis Facultatis Medicae, 142, pp. 7-12; Touboul, P.J., Prati, P., Scarabin, P.-Y., Adrai, V., Thibout, E., Ducimetiere, P., Use of monitoring software to improve the measurement of carotid wall thickness by B-mode imaging (1992) J. Hypertension, 10 (5), pp. 37-41; Gariepy, J., Massonneau, M., Levenson, J., Heudes, D., Simon, A., Evidence for in vivo carotid and femoral wall thickness in human hypertension (1993) J. Hypertension, 22 (1), pp. 111-118. , the Groupe de Prevention Cardio-vasculaire en Medecine du Travail; Selzer, R.H., Hodis, H.N., Kwong-Fu, H., Mack, W.J., Lee, P.L., Liu, C.R., Liu, C.H., Evaluation of computerized edge tracking for quantifying intima-media thickness of the common carotid artery from B-mode ultrasound images (1994) Atherosclerosis, 111, pp. 1-11; Gustavsson, T., Liang, Q., Wendelhag, I., Wikstrand, J., A dynamic programming procedure for automated ultrasonic measurement of the carotid artery (1994) Comput. Cardiol., pp. 297-300; Kozick, R.J., Detecting interfaces on ultrasound images of the carotid artery by dynamic programming (1996) SPIE, 2666, pp. 233-241; Gustavsson, T., Abu-Gharbieh, R., Hamarneh, G., Liang, Q., Implementation and comparison of four different boundary detection algorithms for quantitative ultrasonic measurements of the human carotid artery (1997) Comput. Cardiol., pp. 69-72; Detmer, P., Bashein, G., Martin, R., Matched filter identification of left-ventricle endocardial borders in transesophageal echocardiograms (1990) IEEE Trans. Med. Imaging, 9 (4), pp. 396-404; Liang, Q., Wendelhag, I., Wikstrand, J., Gustavsson, T., A multiscale dynamic programming procedure for boundary detection in ultrasound artery images (2000) IEEE Trans. Med. Imaging, 19 (2), pp. 127-142; Schmidt-Trucksass, A., Cheng, D., Sandrock, M., Schulte-Monting, J., Rauramaa, R., Huonker, M., Burkhardt, H., Computerized analysing system using the active contour in ultrasound measurement of carotid artery intima-media thickness (2001) Clin. Physiol., 5, pp. 561-569; Cheng, D., Schmidt-Trucksass, A., Cheng, K., Sandrock, M., Pu, Q., Burkhardt, H., (1999), pp. 452-457. , Automatic detection of the intimal and the adventitial layers of the common carotid artery wall in ultrasound B-mode images using snakes, in: Int. Conf. on Image Analysis and Processing, B. WernerCheng, D., Schmidt-Trucksass, A., Cheng, K., Burkhardt, H., Using snakes to detect the intimal and adventitial layers of the common carotid artery wall in sonographic images (2002) Comput. Methods Programs Biomed., 67, pp. 27-37; Kass, M., Witkin, A., Terzopoulos, D., Snakes: active contour models (1988) Int. J. Comput. Vis., pp. 321-331; Christodoulou, C.I., Pattichis, C.S., Pantziaris, M., Nicolaides, A., Texture based classification of atherosclerotic carotid plaques (2003) IEEE Trans. Med. Imaging, 22 (7), pp. 902-912; Barratt, D., Ariff, B., Humphries, K., Thom, S., Hughes, A., Reconstruction and quantification of the carotid artery bifurcation from 3-D ultrasound images (2004) IEEE Trans. Med. Imaging, 23 (5), pp. 567-583; Fischler, M.A., Bolles, R.C., Random sample consensus: a paradigm for model fitting with applications to image analysis and automated cartography (1981) Commun. ACM, 24 (6), pp. 381-395; Rossi, A.C., Brands, P.J., Hoeks, A.P.G., Automatic recognition of the common carotid artery in longitudinal ultrasound B-mode scans (2008) Med. Image Anal., 12, pp. 653-665; Zack, G.W., Rogers, W.E., Latt, S.A., Automatic measurement of sister chromatid exchange frequency (1977) J. Histochem. Cytochem., 25 (7), pp. 741-753; Tauber, C., (2005), Filtrage anisotrope robuste et segmentation par b-spline snake: application aux images échographiques, Ph.D. thesis, Institut National Polytechnique de Toulouse, ToulouseYu, Y., Acton, S., Speckle reducing anisotropic diffusion (2002) IEEE Trans. Image Process., 11 (11), pp. 1260-1270; Yu, Y., Acton, S., Edge detection in ultrasound imagery using the instantaneous coefficient of variation (2004) IEEE Trans. Image Process., 13 (12), pp. 1640-1655; Black, M.J., Sapiro, G., Marimont, D.H., Heeger, D., Robust anisotropic diffusion (1998) IEEE Trans. Image Process., 7 (3), pp. 421-432; Rudin, L., Osher, S., Fatemi, E., Nonlinear total variation based noise removal algorithms (1992) Proceedings of the 11th Annual Int. Conf. of the Center for Nonlinear Studies on Experimental Mathematics: Computational Issues in Nonlinear Science, pp. 259-268; Rudin, L., Osher, S., Total variation based image restoration with free local constraints (1994) Proceedings of IEEE Int. Conf. on Image Processing (ICIP'94), vol. 1, pp. 31-35; Canny, J., A computational approach to edge detection (1986) IEEE Trans. Pattern Anal. Mach. Intell., 8 (6), pp. 679-698; Guo, Z., Hall, R.W., Parallel thinning with two-subiteration algorithms (1989) Commun. ACM, 32 (3), pp. 359-373; Burden, R., Faires, J.D., (2000) Numerical Analysis, , Brooks Cole; Forsyth, D.A., Ponce, J., (2003) Computer Vision: A Modern Approach, , Prentice Hall; Marquina, A., Osher, S., Explicit algorithms for a new time dependent model based on level set motion for nonlinear deblurring and noise removal (2000) SIAM J. Sci. Comput., 22 (2), pp. 387-405; Chum, O., Matas, J., Kittler, J., (2003), 81, pp. 236-243. , Locally optimized RANSAC, in: Lecture Notes in Computer Science - Pattern Recognition, Springer Berlin/Heidelberg, Springer LNCSBland, J.M., Altman, D.G., Statistical methods for assessing agreement between two methods of clinical measurement (1986) Lancet, 1 (8476), pp. 307-310
Keywords: Algorithms; article; B scan; B-mode images; Carotid; carotid artery; Carotid Artery Diseases; Carotid Artery, Common; Class II; clinical article; Common carotid artery; Cubic spline; Detection error; echography; Edge map; Female; Gain function; Geometric models; Geometry; human; Humans; Image Interpretation, Computer-Assisted; image processing; Image segmentation; Image sets; Intensity gradients; Longitudinal section; male; Manual segmentation; mathematical model; Medical experts; Medical imaging; Non-linear smoothing; Pattern Recognition, Automated; quantitative analysis; Quantitative evaluation; random sample; Random sample consensus; RANSAC; Semi-automatic segmentation; Splines; Ultrasonic applications; Ultrasonics; Ultrasonography; Ultrasound image; Ultrasound images

Simulations of the NK cell immune synapse reveal that activation thresholds can be established by inhibitory receptors acting locally - Kaplan, A.; Kotzer, S.; Almeida, C.R.; Kohen, R.; Halpert, G.; Salmon-Divon, M.; Köhler, K.; Höglund, P.; Davis, D.M.; Mehr, R. (Journal of ImmunologyJ. Immunol., 2011)
NK cell activation is regulated by a balance between activating and inhibitory signals. To address the question of how these signals are spatially integrated, we created a computer simulation of activating and inhibitory NK cell immunological synapse (NKIS) assembly, implementing either a "quantity-based" inhibition model or a "distance-based" inhibition model. The simulations mimicked the observed molecule distributions in inhibitory and activating NKIS and yielded several new insights. First, the total signal is highly influenced by activating complex dissociation rates but not by adhesion and inhibitory complex dissociation rates. Second, concerted motion of receptors in clusters significantly accelerates NKIS maturation. Third, when the potential of a cis interaction between Ly49 receptors and MHC class I on murine NK cells was added to the model, the integrated signal as a function of receptor and ligand numbers was only slightly increased, at least up to the level of 50% cis-bound Ly49 receptors reached in the model. Fourth, and perhaps most importantly, the integrated signal behavior obtained when using the distance-based inhibition signal model was closer to the experimentally observed behavior, with an inhibition radius of the order 3-10 molecules. Microscopy to visualize Vav activation in NK cells on micropatterned surfaces of activating and inhibitory strips revealed that Vav is only locally activated where activating receptors are ligated within a single NK cell contact. Taken together, these data are consistent with a model in which inhibitory receptors act locally; that is, that every bound inhibitory receptor acts on activating receptors within a certain radius around it. Copyright © 2011 by The American Association of Immunologists, Inc.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JOIMAdoi: 10.4049/jimmunol.1002208PubMed ID: 21690326Language of Original Document: EnglishCorrespondence Address: Mehr, R.; Mina and Everard Goodman Faculty of Life Sciences, Bar-Ilan University, Ramat-Gan 52900, Israel; email: ramit.mehr@biu.ac.ilChemicals/CAS: Vav protein, 282122-55-8; intercellular adhesion molecule 1, 126547-89-5; H-2 Antigens; Histocompatibility Antigens Class I; Intercellular Adhesion Molecule-1, 126547-89-5; KLRK1 protein, human; Lymphocyte Function-Associated Antigen-1; MHC class I-related chain A; NK Cell Lectin-Like Receptor Subfamily A; NK Cell Lectin-Like Receptor Subfamily K; Receptors, KIRReferences: Burgess, S.J., Maasho, K., Masilamani, M., Narayanan, S., Borrego, F., Coligan, J.E., The NKG2D receptor: Immunobiology and clinical implications (2008) Immunol. Res., 40, pp. 18-34;González, S., López-Soto, A., Suarez-Alvarez, B., López-Vázquez, A., López-Larrea, C., NKG2D ligands: Key targets of the immune response (2008) Trends Immunol., 29, pp. 397-403; Vyas, Y.M., Maniar, H., Dupont, B., Cutting edge: Differential segregation of the Src homology 2-containing protein tyrosine phosphatase-1 within the early NK cell immune synapse distinguishes noncytolytic from cytolytic interactions (2002) Journal of Immunology, 168 (7), pp. 3150-3154; Long, E.O., Negative signaling by inhibitory receptors: The NK cell paradigm (2008) Immunol. Rev., 224, pp. 70-84; Ljunggren, H.G., Kärre, K., In search of the 'missing self': MHC molecules and NK cell recognition (1990) Immunol. Today, 11, pp. 237-244; Kane, K.P., Silver, E.T., Hazes, B., Specificity and function of activating Ly-49 receptors (2001) Immunol. Rev., 181, pp. 104-114; Lanier, L.L., Up on the tightrope: Natural killer cell activation and inhibition (2008) Nat. Immunol., 9, pp. 495-502; Radaev, S., Sun, P.D., Structure and function of natural killer cell surface receptors (2003) Annu. Rev. Biophys. Biomol. Struct., 32, pp. 93-114; Vivier, E., Nunes, J.A., Vely, F., Natural killer cell signaling pathways (2004) Science, 306 (5701), pp. 1517-1519. , DOI 10.1126/science.1103478; Yokoyama, W.M., Plougastel, B.F., Immune functions encoded by the natural killer gene complex (2003) Nat. Rev. Immunol., 3, pp. 304-316; Stebbins, C.C., Watzl, C., Billadeau, D.D., Leibson, P.J., Burshtyn, D.N., Long, E.O., Vav1 dephosphorylation by the tyrosine phosphatase SHP-1 as amechanism for inhibition of cellular cytotoxicity (2003) Mol. Cell. Biol., 23, pp. 6291-6299; Bryceson, Y.T., Long, E.O., Line of attack: NK cell specificity and integration of signals (2008) Curr. Opin. Immunol., 20, pp. 344-352; McCann, F.E., Suhling, K., Carlin, L.M., Eleme, K., Taner, S.B., Yanagi, K., Vanherberghen, B., Davis, D.M., Imaging immune surveillance by T cells and NK cells (2002) Immunol. Rev., 189, pp. 179-192; Davis, D.M., Assembly of the immunological synapse for T cells and NK cells (2002) Trends in Immunology, 23 (7), pp. 356-363. , DOI 10.1016/S1471-4906(02)02243-3, PII S1471490602022433; Vyas, Y.M., Mehta, K.M., Morgan, M., Maniar, H., Butros, L., Jung, S., Burkhardt, J.K., Dupont, B., Spatial organization of signal transduction molecules in the NK cell immune synapses during MHC class I-regulated noncytolytic and cytolytic interactions (2001) Journal of Immunology, 167 (8), pp. 4358-4367; Vyas, Y.M., Maniar, H., Lyddane, C.E., Sadelain, M., Dupont, B., Ligand binding to inhibitory killer cell Ig-like receptors induce colocalization with Src homology domain 2-containing protein tyrosine phosphatase 1 and interruption of ongoing activation signals (2004) Journal of Immunology, 173 (3), pp. 1571-1578; Orange, J.S., Formation and function of the lytic NK-cell immunological synapse (2008) Nat. Rev. Immunol., 8, pp. 713-725; Eleme, K., Taner, S.B., Onfelt, B., Collinson, L.M., McCann, F.E., Chalupny, N.J., Cosman, D., Davis, D.M., Cell surface organization of stress-inducible proteins ULBP and MICA that stimulate human NK cells and T cells via NKG2D (2004) J. Exp. Med., 199, pp. 1005-1010; Cebo, C., Da, R.S., Wittnebel, S., Turhan, A.G., Abdelali, J., Caillat-Zucman, S., Bourhis, J.H., Caignard, A., The decreased susceptibility of Bcr/Abl targets to NK cell-mediated lysis in response to imatinib mesylate involves modulation of NKG2D ligands, GM1 expression, and synapse formation (2006) Journal of Immunology, 176 (2), pp. 864-872; Burack, W.R., Lee, K.H., Holdorf, A.D., Dustin, M.L., Shaw, A.S., Cutting edge: Quantitative imaging of raft accumulation in the immunological synapse (2002) J. Immunol., 169, pp. 2837-2841; Harder, T., Engelhardt, K.R., Membrane domains in lymphocytes - From lipid rafts to protein scaffolds (2004) Traffic, 5, pp. 265-275; Laude, A.J., Prior, I.A., Plasma membrane microdomains: Organization, function and trafficking (2004) Mol. Membr. Biol., 21, pp. 193-205; Lou, Z., Jevremovic, D., Billadeau, D.D., Leibson, P.J., A balance between positive and negative signals in cytotoxic lymphocytes regulates the polarization of lipid rafts during the development of cell-mediated killing (2000) J. Exp. Med., 191, pp. 347-354; Pike, L.J., Lipid rafts: Bringing order to chaos (2003) Journal of Lipid Research, 44 (4), pp. 655-667. , DOI 10.1194/jlr.R200021-JLR200; Pizzo, P., Viola, A., Lymphocyte lipid rafts: Structure and function (2003) Curr. Opin. Immunol., 15, pp. 255-260; Rodgers, W., Farris, D., Mishra, S., Merging complexes: Properties of membrane raft assembly during lymphocyte signaling (2005) Trends Immunol., 26, pp. 97-103; Schmitz, G., Grandl, M., Update on lipid membrane microdomains (2008) Curr. Opin. Clin. Nutr. Metab. Care, 11, pp. 106-112; Wright, M.D., Moseley, G.W., Van Spriel, A.B., Tetraspanin microdomains in immune cell signalling and malignant disease (2004) Tissue Antigens, 64 (5), pp. 533-542. , DOI 10.1111/j.1399-0039.2004.00321.x; Vogt, A.B., Spindeldreher, S., Kropshofer, H., Clustering of MHCpeptide complexes prior to their engagement in the immunological synapse: Lipid raft and tetraspan microdomains (2002) Immunol. Rev., 189, pp. 136-151; Lee, S.J.E., Hori, Y., Groves, J.T., Dustin, M.L., Chakraborty, A.K., Correlation of a dynamic model for immunological synapse formation with effector functions: Two pathways to synapse formation (2002) Trends Immunol., 23, pp. 492-499; Giagulli, C., Scarpini, E., Ottoboni, L., Narumiya, S., Butcher, E.C., Constantin, G., Laudanna, C., RhoA and zeta PKC Control Distinct Modalities of LFA-1 Activation by Chemokines: Critical Role of LFA-1 Affinity Triggering in Lymphocyte In Vivo Homing (2004) Immunity, 20 (1), pp. 25-35. , DOI 10.1016/S1074-7613(03)00350-9; Masilamani, M., Nguyen, C., Kabat, J., Borrego, F., Coligan, J.E., CD94/NKG2A inhibits NK cell activation by disrupting the actin network at the immunological synapse (2006) J. Immunol., 177, pp. 3590-3596; Weikl, T.R., Lipowsky, R., Pattern formation during T-cell adhesion (2004) Biophysical Journal, 87 (6), pp. 3665-3678. , DOI 10.1529/biophysj.104.045609; Kotzer, S., Salmon-Divon, M., Kaplan, A., Almeida, C.R., Hoglund, P., Davis, D.M., Mehr, R., Modeling the influence of molecule and cell surface micro-domain distribution on the formation of T cell immunological synapses (2007) Life Science Systems and Applications Workshop, 2007. LISA 2007. IEEE/NIH. 8-9 November, , http://ieeexplore.ieee.org/xpl/freeabs_all.jsp?arnumber=4400878, Available at; Culley, F.J., Johnson, M., Evans, J.H., Kumar, S., Crilly, R., Casasbuenas, J., Schnyder, T., Ushakov, D.S., Natural killer cell signal integration balances synapse symmetry and migration (2009) PLoS Biol., 7, pp. e1000159; Treanor, B., Lanigan, P.M.P., Kumar, S., Dunsby, C., Munro, I., Auksorius, E., Culley, F.J., Neil, M.A.A., Microclusters of inhibitory killer immunoglobulin-like receptor signaling at natural killer cell immunological synapses (2006) J. Cell Biol., 174, pp. 153-161; Back, J., Chalifour, A., Scarpellino, L., Held, W., Stable masking by H-2Dd cis ligand limits Ly49A relocalization to the site of NK cell/target cell contact (2007) Proc. Natl. Acad. Sci. USA, 104, pp. 3978-3983; Back, J., Scarpellino, L., Held, W., Probing the interactions of NK cell receptors with ligand expressed in trans and cis (2010) MethodsMol. Biol., 612, pp. 313-323; Chalifour, A., Scarpellino, L., Back, J., Brodin, P., Devèvre, E., Gros, F., Lévy, F., Held, W., A role for cis interaction between the inhibitory Ly49A receptor and MHC class I for natural killer cell education (2009) Immunity, 30, pp. 337-347; Doucey, M.A., Scarpellino, L., Zimmer, J., Guillaume, P., Luescher, I.F., Bron, C., Held, W., Cis association of Ly49A with MHC class I restricts natural killer cell inhibition (2004) Nat. Immunol., 5, pp. 328-336; Held, W., Mariuzza, R.A., Cis interactions of immunoreceptors with MHC and non-MHC ligands (2008) Nat. Rev. Immunol., 8, pp. 269-278; Scarpellino, L., Oeschger, F., Guillaume, P., Coedert, J.D., Levy, F., Leclercq, G., Held, W., Interactions of Ly49 family receptors with MHC class I ligands in trans and cis (2007) Journal of Immunology, 178 (3), pp. 1277-1284; Saffman, P.G., Delbrück, M., Brownian motion in biological membranes (1975) Proc. Natl. Acad. Sci. USA, 72, pp. 3111-3113; Raychaudhuri, S., Chakraborty, A.K., Kardar, M., Effective membrane model of the immunological synapse (2003) Phys. Rev. Lett., 91, p. 208101; Burroughs, N.J., Wülfing, C., Differential segregation in a cell-cell contact interface: The dynamics of the immunological synapse (2002) Biophys. J., 83, pp. 1784-1796; Coombs, D., Goldstein, B., Effects of the geometry of the immunological synapse on the delivery of effector molecules (2004) Biophysical Journal, 87 (4), pp. 2215-2220. , DOI 10.1529/biophysj.104.045674; Köhler, K., Xiong, S., Brzostek, J., Mehrabi, M., Eissmann, P., Harrison, A., Cordoba, S.P., Gould, K., Matched sizes of activating and inhibitory receptor/ligand pairs are required for optimal signal integration by human natural killer cells (2010) PLoS ONE, 5, pp. e15374; Dykstra, M., Cherukuri, A., Sohn, H.W., Tzeng, S.J., Pierce, S.K., Location is everything: Lipid rafts and immune cell signaling (2003) Annu. Rev. Immunol., 21, pp. 457-481; Horejsí, V., The roles of membrane microdomains (rafts) in T cell activation (2003) Immunol. Rev., 191, pp. 148-164; Fujiwara, T., Ritchie, K., Murakoshi, H., Jacobson, K., Kusumi, A., Phospholipids undergo hop diffusion in compartmentalized cell membrane (2002) Journal of Cell Biology, 157 (6), pp. 1071-1081. , DOI 10.1083/jcb.200202050; Giurisato, E., McIntosh, D.P., Tassi, M., Gamberucci, A., Benedetti, A., T cell receptor can be recruited to a subset of plasma membrane rafts, independently of cell signaling and attendantly to raft clustering (2003) J. Biol. Chem., 278, pp. 6771-6778; Kusumi, A., Koyama-Honda, I., Suzuki, K., Molecular dynamics and interactions for creation of stimulation-induced stabilized rafts from small unstable steady-state rafts (2004) Traffic, 5 (4), pp. 213-230. , DOI 10.1111/j.1600-0854.2004.0178.x; Marwali, M.R., MacLeod, M.A., Muzia, D.N., Takei, F., Lipid rafts mediate association of LFA-1 and CD3 and formation of the immunological synapse of CTL (2004) Journal of Immunology, 173 (5), pp. 2960-2967; Montixi, C., Langlet, C., Bernard, A.M., Thimonier, J., Dubois, C., Wurbel, M.A., Chauvin, J.P., He, H.T., Engagement of T cell receptor triggers its recruitment to low-density detergent-insoluble membrane domains (1998) EMBO J., 17, pp. 5334-5348; Munro, S., Lipid rafts: Elusive or illusive? (2003) Cell, 115, pp. 377-388; Pizzo, P., Giurisato, E., Bigsten, A., Tassi, M., Tavano, R., Shaw, A., Viola, A., Physiological T cell activation starts and propagates in lipid rafts (2004) Immunol. Lett., 91, pp. 3-9; Xavier, R., Brennan, T., Li, Q., McCormack, C., Seed, B., Membrane compartmentation is required for efficient T cell activation (1998) Immunity, 8, pp. 723-732; Filipp, D., Julius, M., Lipid rafts: Resolution of the "fyn problem"? (2004) Mol. Immunol., 41, pp. 645-656; Schade, A.E., Levine, A.D., Lipid raft heterogeneity in human peripheral blood T lymphoblasts: A mechanism for regulating the initiation of TCR signal transduction (2002) J. Immunol., 168, pp. 2233-2239; Janes, P.W., Ley, S.C., Magee, A.I., Aggregation of lipid rafts accompanies signaling via the T cell antigen receptor (1999) J. Cell Biol., 147, pp. 447-461; Hiltbold, E.M., Poloso, N.J., Roche, P.A., MHC class II-peptide complexes and APC lipid rafts accumulate at the immunological synapse (2003) J. Immunol., 170, pp. 1329-1338; Wülfing, C., Tskvitaria-Fuller, I., Burroughs, N., Sjaastad, M.D., Klem, J., Schatzle, J.D., Interface accumulation of receptor/ligand couples in lymphocyte activation: Methods, mechanisms, and significance (2002) Immunol. Rev., 189, pp. 64-83; Poloso, N.J., Roche, P.A., Association of MHC class II-peptide complexes with plasma membrane lipid microdomains (2004) Curr. Opin. Immunol., 16, pp. 103-107; Anderson, H.A., Hiltbold, E.M., Roche, P.A., Concentration of MHC class II molecules in lipid rafts facilitates antigen presentation (2000) Nat. Immunol., 1, pp. 156-162; Meyer Zum Bueschenfelde, C.O., Unternaehrer, J., Mellman, I., Bottomly, K., Regulated recruitment of MHC class II and costimulatory molecules to lipid rafts in dendritic cells (2004) J. Immunol., 173, pp. 6119-6124; Szollosi, J., Horejsi, V., Bene, L., Angelisova, P., Damjanovich, S., Supramolecular Complexes of MHC Class I, MHC Class II, CD20, and Tetraspan Molecules (CD53, CD81, and CD82) at the Surface of a B Cell Line JY (1996) Journal of Immunology, 157 (7), pp. 2939-2946; Leitinger, B., Hogg, N., The involvement of lipid rafts in the regulation of integrin function (2002) Journal of Cell Science, 115 (5), pp. 963-972; Cherukuri, A., Cheng, P.C., Pierce, S.K., The role of the CD19/CD21 complex in B cell processing and presentation of complement-tagged antigens (2001) J. Immunol., 167, pp. 163-172; Sheets, E.D., Holowka, D., Baird, B., Critical role for cholesterol in Lyn-mediated tyrosine phosphorylation of FcepsilonRI and their association with detergent-resistant membranes (1999) Journal of Cell Biology, 145 (4), pp. 877-887. , DOI 10.1083/jcb.145.4.877; Jordan, S., Rodgers, W., T cell glycolipid-enriched membrane domains are constitutively assembled as membrane patches that translocate to immune synapses (2003) Journal of Immunology, 171 (1), pp. 78-87; Kaizuka, Y., Douglass, A.D., Vardhana, S., Dustin, M.L., Vale, R.D., The coreceptor CD2 uses plasma membrane microdomains to transduce signals in T cells (2009) J. Cell Biol., 185, pp. 521-534; Dustin, M.L., Membrane domains and the immunological synapse: Keeping T cells resting and ready (2002) J. Clin. Invest., 109, pp. 155-160; Almeida, C.R., Davis, D.M., Segregation of HLA-C from ICAM-1 at NK cell immune synapses is controlled by its cell surface density (2006) J. Immunol., 177, pp. 6904-6910; Delon, J., The immunological synapse (2000) Curr. Biol., 10, pp. R214; Anton Van Der Merwe, P., Davis, S.J., Shaw, A.S., Dustin, M.L., Cytoskeletal polarization and redistribution of cell-surface molecules during T cell antigen recognition (2000) Semin. Immunol., 12, pp. 5-21; Bossi, G., Trambas, C., Booth, S., Clark, R., Stinchcombe, J., Griffiths, G.M., The secretory synapse: The secrets of a serial killer (2002) Immunol. Rev., 189, pp. 152-160; Endt, J., McCann, F.E., Almeida, C.R., Urlaub, D., Leung, R., Pende, D., Davis, D.M., Watzl, C., Inhibitory receptor signals suppress ligation-induced recruitment of NKG2D to GM1-rich membrane domains at the human NK cell immune synapse (2007) Journal of Immunology, 178 (9), pp. 5606-5611; Gasser, S., Raulet, D.H., Activation and self-tolerance of natural killer cells (2006) Immunol. Rev., 214, pp. 130-142; Rubio, G., Férez, X., Sánchez-Campillo, M., Gálvez, J., Martí, S., Verdú, R., Hernández-Caselles, T., García-Peñarrubia, P., Cross-linking of MHC class I molecules on human NK cells inhibits NK cell function, segregates MHC I from the NK cell synapse, and induces intracellular phosphotyrosines (2004) J. Leukoc. Biol., 76, pp. 116-124; Kaizuka, Y., Douglass, A.D., Varma, R., Dustin, M.L., Vale, R.D., Mechanisms for segregating T cell receptor and adhesion molecules during immunological synapse formation in Jurkat T cells (2007) Proc. Natl. Acad. Sci. USA, 104, pp. 20296-20301; Brodin, P., Lakshmikanth, T., Mehr, R., Johansson, M.H., Duru, A.D., Achour, A., Salmon-Divon, M., Johansson, S., Natural killer cell tolerance persists despite significant reduction of self MHC class I on normal target cells in mice (2010) PLoS ONE, 5, pp. e1317; Carlin, L.M., Eleme, K., McCann, F.E., Davis, D.M., Intercellular transfer and supramolecular organization of human leukocyte antigen C at inhibitory natural killer cell immune synapses (2001) J. Exp. Med., 194, pp. 1507-1517; Fassett, M.S., Davis, D.M., Valter, M.M., Cohen, G.B., Strominger, J.L., Signaling at the inhibitory natural killer cell immune synapse regulates lipid raft polarization but not class I MHC clustering (2001) Proc. Natl. Acad. Sci. USA, 98, pp. 14547-14552; Faure, M., Barber, D.F., Takahashi, S.M., Jin, T., Long, E.O., Spontaneous clustering and tyrosine phosphorylation of NK cell inhibitory receptor induced by ligand binding (2003) J. Immunol., 170, pp. 6107-6114; Standeven, L.J., Carlin, L.M., Borszcz, P., Davis, D.M., Burshtyn, D.N., The actin cytoskeleton controls the efficiency of killer Ig-like receptor accumulation at inhibitory NK cell immune synapses (2004) J. Immunol., 173, pp. 5617-5625; Abeyweera, T.P., Merino, E., Huse, M., Inhibitory signaling blocks activating receptor clustering and induces cytoskeletal retraction in natural killer cells (2011) J. Cell Biol., 192, pp. 675-690; Labadia, M.E., Jeanfavre, D.D., Caviness, G.O., Morelock, M.M., Molecular regulation of the interaction between leukocyte function-associated antigen-1 and soluble ICAM-1 by divalent metal cations (1998) J. Immunol., 161, pp. 836-842; Tominaga, Y., Kita, Y., Satoh, A., Asai, S., Kato, K., Ishikawa, K., Horiuchi, T., Takashi, T., Affinity and kinetic analysis of the molecular interaction of ICAM-1 and leukocyte function-associated antigen-1 (1998) Journal of Immunology, 161 (8), pp. 4016-4022; Maenaka, K., Van Der Merwe, P.A., Stuart, D.I., Jones, E.Y., Sondermann, P., The human low affinity Fcgamma receptors IIa, IIb, and III bind IgG with fast kinetics and distinct thermodynamic properties (2001) J. Biol. Chem., 276, pp. 44898-44904; Dustin, M.L., Ferguson, L.M., Chan, P.Y., Springer, T.A., Golan, D.E., Visualization of CD2 interaction with LFA-3 and determination of the twodimensional dissociation constant for adhesion receptors in a contact area (1996) J. Cell Biol., 132, pp. 465-474; Sloan-Lancaster, J., Presley, J., Ellenberg, J., Yamazaki, T., Lippincott-Schwartz, J., Samelson, L.E., ZAP-70 association with T cell receptor zeta (TCRzeta): Fluorescence imaging of dynamic changes upon cellular stimulation (1998) J. Cell Biol., 143, pp. 613-624; Von Essen, M., Bonefeld, C.M., Siersma, V., Rasmussen, A.B., Lauritsen, J.P.H., Nielsen, B.L., Geisler, C., Constitutive and ligand-induced TCR degradation (2004) Journal of Immunology, 173 (1), pp. 384-393; Groves, J.T., Wulfing, C., Boxer, S.G., Electrical manipulation of glycan-phosphatidyl inositol-tethered proteins in planar supported bilayers (1996) Biophys. J., 71, pp. 2716-2723; Krogsgaard, M., Li, Q.J., Sumen, C., Huppa, J.B., Huse, M., Davis, M.M., Agonist/endogenous peptide-MHC heterodimers drive T cell activation and sensitivity (2005) Nature, 434, pp. 238-243; Dimasi, N., Sawicki, M.W., Reineck, L.A., Li, Y., Natarajan, K., Margulies, D.H., Mariuzza, R.A., Crystal structure of the Ly49I natural killer cell receptor reveals variability in dimerization mode within the Ly49 family (2002) J. Mol. Biol., 320, pp. 573-585; Natarajan, K., Boyd, L.F., Schuck, P., Yokoyama, W.M., Eliat, D., Margulies, D.H., Interaction of the NK cell inhibitory receptor Ly49A with H-2Dd: Identification of a site distinct from the TCR site (1999) Immunity, 11, pp. 591-601; O'Callaghan, C.A., Cerwenka, A., Willcox, B.E., Lanier, L.L., Bjorkman, P.J., Molecular competition for NKG2D: H60 and RAE1 compete unequally for NKG2D with dominance of H60 (2001) Immunity, 15, pp. 201-211; Borrego, F., Masilamani, M., Marusina, A.I., Tang, X., Coligan, J.E., The CD94/NKG2 family of receptors: From molecules and cells to clinical relevance (2006) Immunol. Res., 35, pp. 263-278
Keywords: animal cell; animal experiment; Animals; antigen recognition; article; cell maturation; cell membrane; Computer simulation; controlled study; dissociation; H-2 Antigens; Histocompatibility Antigens Class I; HLA antigen; HLA C antigen; Humans; immunological synapse; Immunological Synapses; intercellular adhesion molecule 1; Intercellular Adhesion Molecule-1; killer cell immunoglobulin like receptor 2DL1; Killer Cells, Natural; lymphocyte activation; lymphocyte function associated antigen 1; Lymphocyte Function-Associated Antigen-1; major histocompatibility antigen class 1; Membrane Microdomains; Mice; Models, Immunological; mouse; natural killer cell; natural killer cell receptor NKG2D; NK Cell Lectin-Like Receptor Subfamily A; NK Cell Lectin-Like Receptor Subfamily K; nonhuman; priority journal; protein assembly; Receptors, KIR; signal transduction; steady state; Vav protein

Systemic delivery of bone marrow-derived mesenchymal stromal cells diminishes neuropathology in a mouse model of Krabbe's disease - Miranda, C.O.; Teixeira, C.A.; Liz, M.A.; Sousa, V.F.; Franquinho, F.; Forte, G.; Di Nardo, P.; Pinto-Do-Ó, P.; Sousa, M.M. (Stem Cells, 2011)
Cited By (since 1996):4Export Date: 2 October 2013Source: Scopus

Access to computerised analysis of intrapartum cardiotocographs improves clinicians' prediction of newborn umbilical artery blood pH - Costa, A.; Santos, C.; Ayres-de-Campos, D.; Costa, C.; Bernardes, J. (BJOG: An International Journal of Obstetrics and GynaecologyBJOG Int. J. Obstet. Gynaecol., 2010)
Objective To evaluate the impact of access to computerised cardiotocograph (CTG) analysis on reproducibility and accuracy of clinicians' predictions of umbilical artery blood pH (UAB pH) and 5-minute Apgar score. Design Prospective evaluation of pre-recorded cases. Setting A tertiary-care university hospital. Population From databases of intrapartum CTGs acquired in singleton term pregnancies, 204 tracings with low signal loss and short time interval to delivery were consecutively selected. Methods Tracings were randomly assigned to computer analysis by the Omniview-SisPorto 3.5 ® system (study group n = 104) or to no analysis (control group n = 100). Three experienced clinicians evaluated all tracing printouts independently and were asked to predict the newborns' UAB pH and 5-minute Apgar scores from them. Main outcome measures Interobserver agreement (measured by the intraclass correlation coefficient [ICC]) and accuracy in prediction of neonatal outcomes with 95% CI. Results Agreement on prediction of UAB pH was significantly higher in the study group (ICC = 0.70; 95% CI 0.61-0.77) than in the control group (ICC = 0.43; 95% CI 0.21-0.60), and a trend towards better agreement was also seen in estimation of 5-minute Apgar scores (ICC = 0.55; 95% CI 0.38-0.68 versus ICC = 0.43; 95% CI 0.25-0.57). Observers predicted UAB pH values correctly within a 0.10 margin in 70% of cases in the study group (95% CI 0.61-0.79) versus 46% in the control group (95% CI 0.35-0.56). They predicted 5-minute Apgar scores within a margin of one in 81% of cases in the study group (95% CI 0.73-0.88) and in 70% of cases in the control group (95% CI 0.61-0.79). Conclusions Prediction of UAB pH is more reproducible and accurate when clinicians have access to computerised analysis of CTGs. © RCOG 2010 BJOG An International Journal of Obstetrics and Gynaecology.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: BIOGFdoi: 10.1111/j.1471-0528.2010.02645.xPubMed ID: 20618316Language of Original Document: EnglishCorrespondence Address: Costa, A.; Departamento de Ginecologia e Obstetrícia, Faculdade de Medicina da Universidade Do Porto, Alameda Hernani Monteiro, 4200-319 Porto, Portugal; email: cosantonia@gmail.comReferences: Ayres-De-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-10;Donker, D.K., Van Geijn, H.P., Hasman, A., Interobserver variation in the assessment of fetal heart rate recordings (1993) Eur J Obstet Gynecol Reprod Biol, 52, pp. 21-8; Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-65; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-5; Ayres-De-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto ® 3.5 - A central fetal monitoring station with online alerts based on computerized cardiotocogram+ST event analysis (2008) J Perinat Med, 36, pp. 260-4; Costa, A., Ayres-De-Campos, D., Costa, F., Santos, C., Bernardes, J., Prediction of neonatal acidemia by computer analysis of fetal heart rate and ST event signals (2009) Am J Obstet Gynecol, 201, pp. 464e1-6. , Jun 17. [Epub ahead of print]; Westerhuis, M., Van Horen, E., Kwee, A., Van Dertweel, I., Visser, G., Moons, K., Inter- and intra-observer agreement of intrapartum ST analysis of the fetal electrocardiogram in women monitored by STAN (2009) BJOG, 116, pp. 545-51; Ayres-De-Campos, D., Bernardes, J., Marsalb, K., Nickelsen, C., Makarainend, L., Banfield, P., Can the reproducibility of fetal heart rate baseline estimation be improved? (2004) Eur J Obstet Gynecol Reprod Biol, 112, pp. 49-54; Huch, A., Huch, C., Rooth, G., Guidelines for blood sampling and measurement of pH and blood gas values in Obstetrics (1994) Eur J Obstet Gynecol Reprod Biol, 54, pp. 165-75; Umbilical artery blood acid-base analysis (1996) Int J Gynecol Obstet, 52, pp. 305-10. , ACOG technical bulletin; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: A time for quality data (1994) Br J Obstet Gynaecol, 101, pp. 1054-63; Costa-Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynaecology: Inappropriateness, controversies and consequences (2005) BJOG, 112, pp. 667-9; Bland, J.M., Altman, D.G., Agreement between methods of measurement with multiple observations per individual (2007) J Biopharm Stat, 17, pp. 571-82; Chauhan, S.P., Klauser, C.K., Woodring, T.C., Sanderson, M., Magann, E.F., Morrison, J.C., Intrapartum nonreassuring fetal heart rate tracing and prediction of adverse outcomes: Interobserver variability (2008) Am J Obstet Gynecol, 199, pp. 623e1-e5; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., The value of computer assessment compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464
Keywords: access to information; Apgar score; arterial pH; article; Cardiotocography; clinical competence; computer analysis; computerised analysis; controlled study; delivery; Diagnosis, Computer-Assisted; diagnostic accuracy; Female; Fetal Blood; Fetal heart rate; Fetal monitoring; Gestational Age; human; Humans; Hydrogen-Ion Concentration; Infant, Newborn; male; neonatal acidaemia; Neonatology; newborn; observer variation; outcome assessment; prediction; Pregnancy; priority journal; Prospective Studies; prospective study; reproducibility; Umbilical Arteries; umbilical artery; university hospital

Assessment of Disagreement: A New Information-Based Approach - Costa-Santos, C.; Antunes, L.; Souto, A.; Bernardes, J. (Annals of EpidemiologyAnn. Epidemiol., 2010)
Purpose: Disagreement on the interpretation of diagnostic tests and clinical decisions remains an important problem in medicine. As no strategy to assess agreement seems to be fail-safe to compare the degree of agreement, or disagreement, we propose a new information-based approach to assess disagreement. Methods: The sum over all logarithms of possible outcomes of a variable is a valid measure of the amount of information contained in the variable. The proposed measure is based on the amount of information contained in the differences between two observations. This measure is normalized and satisfies the flowing properties: it is a metric, scaled invariant and it has differential weighting. Results: Two real examples and a simulation were used to illustrate the usefulness of the proposed measure to compare the degree of disagreement. Conclusions: Used as complement to the existing methods, we believe our approach can be useful to compare the degree of disagreement among different populations. © 2010 Elsevier Inc.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: ANNPEdoi: 10.1016/j.annepidem.2010.02.011Language of Original Document: EnglishCorrespondence Address: Costa-Santos, C.; Biostatistics and Medical Informatics Department, Faculty of Medicine, University of Porto, Al. Prof. Hernâni Monteiro, 4200-319 Porto, Portugal; email: csantos@med.up.ptReferences: Bland, M., (2000) An introduction to medical statistics, , Oxford University Press, Oxford;Costa Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynecology: inappropriateness, controversies and consequences (2005) Br J Obstet Gynaecol, 112, pp. 667-669; Gow, R.M., Barrowman, N.J., Lai, L., Moher, D., A review of five cardiology journals found that observer variability of measured variables was infrequently reported (2008) J Clin Epidemiol, 61, pp. 394-401; Luiz, R.R., Szklo, M., More than one statistical strategy to assess agreement of quantitative measurements may usefully be reported (2005) J Clin Epidemiol, 58, pp. 215-216; de Vet, H., Observer reliability and agreement (1999) Encyclopedia of Biostatistics, pp. 3123-3127. , Wiley, Chichester, P. Armitage, T. Colton (Eds.); Shrout, P.E., Fleiss, J.L., Intraclass correlation: uses in assessing rater reliability (1979) Psychol Bull, 88, pp. 420-428; Burdock, E.I., Fleiss, J.L., Hardesty, A.S., A new view of interobserver agreement (1963) Psychol Bull, 16, pp. 373-384; McGraw, K.O., Wong, S.P., Forming inferences about some intraclass correlation coefficients (1996) Psychol Methods, 1, pp. 30-46; Muller, R., Buttner, P., A critical discussion of intraclass correlation coefficients (1994) Stat Med, 13, pp. 2465-2476; Steiner, D.L., Norman, G.R., (2003) Health measurements scales. A practical guide to their development and use, , Oxford University Press, Oxford; Lee, D., Koh, D., Ong, C.N., Statistical evaluation of the agreement between two methods for measuring a quantitative variable (1989) Comput Biol Med, 19, pp. 61-70; Lin, L.K., A concordance correlation coefficient to evaluate reproducibility (1989) Biometrics, 45, pp. 255-268; Nickerson, C.A.E., A note on " A Concordance Correlation Coefficient to Evaluate Reproducibility" (1997) Biometrics, 53, pp. 1503-1507; Atkinson, G., Nevill, A., Comment on the " Use of Concordance Correlation to Assess the Agreement between Two Variables" (1997) Biometrics, 53, pp. 775-777; Bland, J.M., Altman, D.G., Statistical methods for assessing two methods of clinical measurement (1986) Lancet, 1, pp. 307-310; Luiz, R.R., Costa, A.J., Kale, P.L., Werneck, G.L., Assessment of agreement of a quantitative variable: a new graphical approach (2003) J Clin Epidemiol, 56, pp. 963-967; Monti, K.L., Folded empirical distribution function curves-mountain plots (1995) Am Stat, 33, pp. 525-527; Shannon, I., A mathematical theory of communication (1948) Bell System Tech J, 27, pp. 379-423. , 623-656; Bland, J.M., Altaman, D.G., Measuring agreement in method comparison studies (1999) Stat Methods Med Res, 8, pp. 135-160
Keywords: analysis of variance; Apgar score; article; Blood Pressure Determination; blood pressure measurement; correlation coefficient; human; Humans; information science; Information Theory; intermethod comparison; mathematical computing; measurement error; medical research; metric system; Models, Statistical; observer variation; priority journal; probability; process model; reliability; Reproducibility of Results; scale up; standard; Statistical analysis; statistical model; statistics; Statistics as Topic; systolic blood pressure; validity; variance

Ceramics for dental restorations - an introduction - Santander, S.A.; Vargas, A.P.; Escobar, J.S.; Monteiro, F.J.; Tamayo, L.F.R. (Una perspectiva de las cerámicas para restauraciones dentalesDYNADYNA, 2010)
Dental ceramics are the preferred materials for oral restoration due to some characteristics, such as adequate esthetics, high fracture strength and chemical stability. Currently, dental professionals have a large amount of ceramic systems to choose from, all of them having small differences regarding their chemistry, processing temperatures, mechanical strength and clinical applications. These differences lead to classification systems that are difficult to understand by professionals outside the dental field. The aim of this work is to review the current dental ceramic systems and present them from a compositional perspective to assure the comprehension of these materials by professionals who belong to the Biomedical Engineering field. A great effort was made to avoid classification methods imposed by manufacturers and to obtain a quick compilation of available information from the literature allowing the reader to have a general view of the stateoftheart on dental ceramics.
Keywords: Ceramic systems; Feldspathic porcelain; Glassceramics; Leucite; Mechanical and physical properties; Zirconium oxide

Characterization of two DLC coatings for joint prosthesis: The role of albumin on the tribological behavior - Carapeto, A.P.; Serro, A.P.; Nunes, B.M.F.; Martins, M.C.L.; Todorovic, S.; Duarte, M.T.; André, V.; Colaço, R.; Saramago, B. (Surface and Coatings TechnologySurf. Coat. Technol., 2010)
A commonly used strategy for reduction of wear and friction of the sliding surfaces in prosthetic pairs is the use of hard coatings. DLCs (diamond like carbons) offer a promising solution, because these coatings, already used in other biomedical applications, exhibit a unique combination of chemical inertness, mechanical and tribological properties. In the present work we investigated the role of albumin, the most abundant protein in the periprosthetic fluid, on the tribological behavior of two DLCs with different compositions, against ultra-high molecular weight polyethylene (UHMWPE). The results are compared with those obtained with uncoated stainless steel surfaces. We have characterized the coatings by atomic force microscopy, X-ray diffraction, Raman spectroscopy, ultramicrohardness and wettability measurements. The adsorption of albumin onto the surfaces was investigated by ellipsometry and using a quartz crystal microbalance. Both DLCs adsorb a larger amount of protein than stainless steel. The tribological tests were performed in microtribometer aiming for a deeper understanding of the tribological mechanisms which occur at the submicrometric contact scale. Results showed no significant differences between the tribological behavior of the two coatings. Under the tested conditions, the tribological performance does not improve significantly with the application of the DLCs. Moreover, the presence of albumin on the lubricant leads to higher friction of the polymer against all counterfaces. This effect was attributed to the formation of bridges between the two sliding surfaces by the denaturated protein. The significant differences in the adsorbed amounts of protein onto the stainless steel and the two types of DLCs did not affect considerably the tribological behavior of these materials. © 2010 Elsevier B.V.
Cited By (since 1996): 6Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.surfcoat.2010.04.022Language of Original Document: EnglishCorrespondence Address: Serro, A.P.; Centro de Química Estrutural, Complexo I, Instituto Superior Técnico, Av. Rovisco Pais, TU Lisbon, 1049-001 Lisboa, Portugal; email: anapaula.serro@ist.utl.ptReferences: Donnet, C., Erdemir, A., (2009), Springer Science & Business Media, New YorkGutensohn, K., Beythien, C., Bau, J., Fenner, T., Grewe, P., Koester, R., Padmanaban, K., Kuehnl, P., (2000) Thromb. Res., 99, p. 577;Cadosch, D., Chan, E., Gautschi, O.P., Simmen, H.-P., Filgueira, L., (2009) J. Orthop. Res., 27, p. 841; Gillespie, W.L., Frampton, C.M.A., Henderson, R.J., Ryan, P.M., (1988) J. Bone Joint Surg. Br., 70 (4), p. 539; Roy, R.K., Lee, K.-R., (2007) J. Biomed. Mater. Res. B Appl. Biomater., 83 B (1), p. 72; Alakoski, E., Tiainen, V.-M., Soininen, A., Konttinen, Y.T., (2008) Open Orthop. J., 2, p. 43; Fisher, J., Firkins, P., Reeves, E.A., Hailey, J.L., Isaac, G.H., (1995) Proc. Inst. Mech. Eng., 209, p. 263; Sheeja, D., Tay, B.K., Lau, S.P., Nung, L.N., (2001) Surf. Coat. Technol., p. 410; Tiainen, V.-M., (2001) Diamond Relat. Mater., 10 (2), p. 153; Oñate, J.I., Comin, M., Braceras, I., Garcia, A., Viviente, J.L., Brizuela, M., Garagorri, N., Alava, J.I., (2001) Surf. Coat. Technol., p. 1056; Shi, B., Ajayi, O.O., Fenske, G., Erdemir, A., Liang, H., (2003) Wear, 255, p. 1015; Lappalainen, R., Selenius, M., Anttila, A., Konttinen, Y.T., Santavirta, S.S., (2003) J. Appl. Biomater., 66 B, p. 410; Sheeja, D., Tay, B.K., Nung, L.N., (2004) Diamond Relat. Mater., 13, p. 184; Xu, T., Pruitt, L., (1999) J. Mater. Sci. Mater. Med., 10, p. 83; Lappalainen, R., Anttila, A., Heinonen, H., (1998) Clin. Orthop., 352, p. 118; Saikko, V., Ahlroos, T., Calonius, O., Keränen, J., (2001) Biomaterials, 22, p. 1507; Sheeja, D., Tay, B.K., Lau, S.P., Nung, L.N., (2001) Surf. Coat. Technol., 146, p. 410; Affatato, S., Frigo, M., Toni, A., (2000) J. Biomed. Mater. Res., 53 (3), p. 221; Scholes, S.C., Unsworth, A., Goldsmit, A.A.J., (2000) Phys. Med. Biol., 45, p. 3721; Ahlroos, T., Saikko, V., (1997) Wear, 211, p. 113; Fedel, M., Motta, A., Maniglio, D., (2009) J. Biomed. Mater. Res., 90 B (1), p. 338; Lousiniana, S., Logothetidis, S., Laskarakisa, A., Gioti, M., (2007) Biomolec. Eng., 24 (1), p. 107; Li, B.G., Kang, Y.Q., Yin, G.F., Zheng, C.Q., (2007) Key Eng. Mater. High-Performance Ceram. IV, p. 1814; Fenske, G.R., (2009) Presented to Chicago Section STLE meeting, , M; Eryilmaz, O.L., Erdemir, A., (2008) Surf. Coat. Technol., 203, p. 750; Gerwin, N., Hops, C., Lucke, A., (2006) Adv. Drug Deliv. Rev., 58 (2), p. 226; Visco, A.M., Torrisi, L., Campo, N., Emanuele, U., Trifiro, A., Trimarchi, M., (2009) J. Biomed. Mater. Res. B Appl. Biomater., 89 B, p. 55; Ferrari, A.C., Robertson, J., (2001) Phys. Rev. B, 64, p. 75414; Ferrari, A.C., Robertson, J., (2000) Phys. Rev. B, 61, p. 14095; Zhou, B., Prorok, B.C., Erdemir, A., Eryilmaz, O., (2007) Diamond Relat. Mater., 16, p. 342; Zhou, B., Prorok, B.C., Erdemir, A., Eryilmaz, O., (2006) Diamond Relat. Mater., 15, p. 2051; Beeman, D., Silverman, J., Lynds, R., Anderson, M.R., (1984) Phys. Rev. B., 30 (2), p. 870; Colaço, R., Serro, A.P., Eryilmaz, O.L., Erdemir, E., (2009) J. Phys. D Appl. Phys., 42, p. 85307; Paul, R., Das, S.N., Dalui, S., Gayen, R.N., Roy, R.K., Bhar, R., Pal, A.K., (2008) J. Phys. D Appl. Phys., 41 (5), p. 55309; Serro, A.P., Fernandes, A.C., Saramago, B., (1997) Colloids Surf. A Physicochem. Eng. Aspects, 125, p. 209; Serro, A.P., Degiampietro, K., Colaço, R., Saramago, B., (2010) Saramago, Adsorption of albumin and sodium hyaluronate on UHMWPE: A QCM-D and AFM study, Colloids and Surfaces B: Biointerfaces, 78, p. 1; de Feijter, J.A., Benjamins, J., Veer, F.A., (1978) Biopolymers, 17, p. 1759; Gispert, M.P., Serro, A.P., Colaço, R., Saramago, B., (2008) Surf. Int. Anal., 40 (12), p. 1529; Hook, F., Kasemo, B., Nylander, T., Fant, C., Sott, K., Elwing, H., (2001) Anal. Chem., 73 (24), p. 5796; Hook, F., Voros, J., Rodahl, M., Kurrat, R., Boni, P., Ramsden, J.J., Textor, M., Kasemo, B., (2002) Colloids Surf. B Biointerfaces, 24, p. 155; Colaço, R., Gispert, M.P., Serro, A.P., Saramago, B., (2007) Tribol. Lett., 26 (2), p. 119; Gispert, M.P., Serro, A.P., Colaço, R., Saramago, B., (2006) Wear, 260, p. 149; Serro, A.P., Completo, C., Colaço, R., Dos Santos, F., Lobato da Silva, C., Cabral, J.M.S., Araújo, H., Saramago, B., (2009) Surf. Coat. Technol., 203, p. 3701; Widmer, M.R., Heuberger, M., Vörös, J., Spencer, N.D., (2001) Tribol. Lett., 10, p. 111; Chen, X.M., Jin, Z.M., Fisher, J., (2008) Proc. Inst. Mech. Eng. Part J. Eng. Tribol., 222 (3), p. 513; Kumar, P., Oka, M., Ikeuchi, K., Shimizu, K., Yamamuro, T., Okumura, H., Kotoura, Y., (1991) J. Biomater. Mater. Res., 25, p. 813; Roba, M., Naka, M., Gautier, E., Spencer, N.D., Crockett, R., (2009) Biomaterials, 30, p. 2072; Karuppiah, K.S.K., Sundararajan, S., Xu, Z.-H., Li, X., (2006) Tribol. Lett., 22 (2), p. 181; Yang, C.-B., Fang, H.-W., Liu, H.-L., Chang, C.-H., Hsieh, M.-C., Lee, W.-M., Huang, H.-T., (2006) Chem. Phys. Lett., 431, p. 380; Fang, H.-W., Wang, H.-C., Tsai, T.-H., Tsai, W.-B., Hou, S.-Y., Liu, H.-L., Lee, W.-H., Huang, C.-H., (2008) J. Appl. Polym. Sci., 108, p. 2428; Zappone, B., Rosenberg, K.J., Israelachvili, J., (2007) Tribol. Lett., 26 (3), p. 191; Grill, A., (1997) Surf. Coat. Technol., (1-3), p. 507; Fontaine, J., Belin, M., Le Mogne, T., Grill, A., (2004) Tribol. Int., 37, p. 869; Sanchez-Lopez, J.C., Erdemir, A., Donnet, C., Rojas, T.C., (2003) Surf. Coat. Technol., 163, p. 444; Robertson, J., (2002) Mater. Sci. Eng., 37, p. 129
Keywords: Adsorbed amount; Adsorption; Albumin adsorption; Atomic force microscopy; Atomic spectroscopy; Biomedical applications; Chemical inertness; Corrosion resistant alloys; Diamond like carbon; DLC coatings; Friction; Hard coatings; Joint prostheses; Mechanical and tribological properties; Mechanical properties; Microtribology; Microtribometer; Nonmetallic matrix composites; Oxide minerals; Polyethylenes; Proteins; Quartz; Raman spectroscopy; Scanning electron microscopy; Sliding surface; Stainless steel; Stainless steel surface; Steel corrosion; Surfaces; Tribological behaviors; Tribological mechanism; Tribological performance; Tribological tests; Tribology; UHMW-PE; UHMWPE; Ultramicrohardness; Wear and friction; Wettability measurements; X ray diffraction

Chitosan-based gene delivery vectors targeted to the peripheral nervous system - Oliveira, H.; Pires, L.R.; Fernandez, R.; Martins, M.C.L.; Simões, S.; Pêgo, A.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
A non-toxic, targeted, simple and efficient system that can specifically transfect peripheral sensorial neurons can pave the way towards the development of new therapeutics for the treatment of peripheral neuropathies. In this study chitosan (CH), a biodegradable polymer, was used as the starting material in the design of a multicomponent vector targeted to the peripheral nervous system (PNS). Polycation-DNA complexes were optimized using imidazole-and thiol-grafted CH (CHimiSH), in order to increase transfection efficiency and allow the formation of ligand conjugated nanocomplexes, respectively. The 50 kDa non-toxic fragment from the tetanus toxin (HC), shown to interact specifically with peripheral neurons and undergo retrograde transport, was grafted to the binary complex via a bi-functional poly(ethylene glycol) (HC-PEG) reactive for the thiol moieties present in the complex surface. The targeting of the developed nanocomplexes was assessed by means of internalization and transfection studies in the ND7/23 (neuronal) vs. NIH 3T3 (fibroblast) cell lines. Targeted transfection was further confirmed in dorsal root ganglion dissociated primary cultures. A versatile, multi-component nanoparticle system that successfully targets and transfects neuronal cell lines, as well as dorsal root ganglia (DRG) primary neuron cultures was obtained for the 1.0 (w/w) HC-PEG/DNA formulation. © 2010 Wiley Periodicals, Inc.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32874PubMed ID: 20734332Language of Original Document: EnglishCorrespondence Address: Pêgo, A. P.; INEB, Instituto de Engenharia Biomédica, Universidade Do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: apego@ineb.up.ptChemicals/CAS: DNA, 9007-49-2; chitosan, 9012-76-4; imidazole, 1467-16-9, 288-32-4; macrogol, 25322-68-3; Cations; Chitosan, 9012-76-4; DNA, 9007-49-2; Polyethylene GlycolsTradenames: Chimarin, medicarb, SwedenManufacturers: medicarb, SwedenReferences: Rodriguez, F.J., Valero-Cabre, A., Navarro, X., Regeneration and functional recovery following peripheral nerve injury (2004) Drug Discov Today, 1, pp. 177-185;Apfel, S.C., Neurotrophic factors in peripheral neuropathies: Therapeutic implications (1999) Brain Pathol, 9, pp. 393-413; Apfel, S.C., Is the therapeutic application of neurotrophic factors dead? (2002) Ann Neurol, 51, pp. 8-11; Glorioso, J.C., Mata, M., Fink, D.J., Therapeutic gene transfer to the nervous system using viral vectors (2003) J Neurovirol, 9, pp. 165-172; Fishman, P.S., Carrigan, D.R., Retrograde transneuronal transfer of the C-fragment of tetanus toxin (1987) Brain Res, 406, pp. 275-279; Evinger, C., Erichsen, J.T., Transsynaptic retrograde transport of fragment C of tetanus toxin demonstrated by immunohistochemical localization (1986) Brain Res, 380, pp. 383-388; Figueiredo, D.M., Hallewell, R.A., Chen, L.L., Fairweather, N.F., Dougan, G., Savitt, J.M., Parks, D.A., Fishman, P.S., Delivery of recombinant tetanus-superoxide dismutase proteins to central nervous system neurons by retrograde axonal transport (1997) Exp Neurol, 145 (2 PART 1), pp. 546-554; Fishman, P.S., Savitt, J.M., Farrand, D.A., Enhanced CNS uptake of systemically administered proteins through conjugation with tetanus C-fragment (1990) J Neurol Sci, 98, pp. 311-325; Coen, L., Osta, R., Maury, M., Brulet, P., Construction of hybrid proteins that migrate retrogradely and transynaptically into the central nervous system (1997) Proc Natl Acad Sci USA, 94, pp. 9400-9405; Knight, A., Carvajal, J., Schneider, H., Coutelle, C., Chamberlain, S., Fairweather, N., Non-viral neuronal gene delivery mediated by the HC fragment of tetanus toxin (1999) Eur J Biochem, 259, pp. 762-769; Oliveira, H., Fernandez, R., Pires, L.R., Simões, S., Martins, M.C.L., Barbosa, M.A., Pêgo, A.P., Targeted gene delivery into peripheral sensorial neurons mediated by self-assembled vectors composed of poly(ethilenimine) and tetanus toxin fragment c (2010) J Control Release, 143, pp. 350-358; Neu, M., Fischer, D., Kissel, T., Recent advances in rational gene transfer vector design based on poly(ethylene imine) and its derivatives (2005) J Gene Med, 7, pp. 992-1009; Tang, G.P., Guo, H.Y., Alexis, F., Wang, X., Zeng, S., Lim, T.M., Ding, J., Wang, S., Low molecular weight polyethylenimines linked by beta-cyclodextrin for gene transfer into the nervous system (2006) J Gene Med, 8, pp. 736-744; Chollet, P., Favrot, M.C., Hurbin, A., Coll, J.L., Side-effects of a systemic injection of linear polyethylenimine-DNA complexes (2002) J Gene Med, 4, pp. 84-91; Shi, C., Zhu, Y., Ran, X., Wang, M., Su, Y., Cheng, T., Therapeutic potential of chitosan and its derivatives in regenerative medicine (2006) J Surg Res, 133, pp. 185-192; Mansouri, S., Lavigne, P., Corsi, K., Benderdour, M., Beaumont, E., Fernandes, J.C., Chitosan-DNA nanoparticles as non-viral vectors in gene therapy: Strategies to improve transfection efficacy (2004) Eur J Pharm Biopharm, 57, pp. 1-8; Moreira, C., Oliveira, H., Pires, L.R., Simoes, S., Barbosa, M.A., Pego, A.P., Improving chitosan-mediated gene transfer by the introduction of intracellular buffering moieties into the chitosan backbone (2009) Acta Biomater, 5, pp. 2995-3006; Verma, A., Stellacci, F., Effect of surface properties on nanoparticle-cell interactions (2010) Small, 6, pp. 12-21; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; (1987) Guideline on Validation of the Limulus Amebocyte Lysate Test As An End-product Endotoxin Test for Human and Animal Parental Drugs, Biological Products, and Medical Devices, , US Department of Health and Human Services. US Department of Health and Human Services; MacUlotti, K., Genta, I., Perugini, P., Imam, M., Bernkop-Schnurch, A., Pavanetto, F., Preparation and in vitro evaluation of thiolated chitosan microparticles (2005) J Microencapsul, 22, pp. 459-470; Mao, H., Roy, K., Troung-Le, V.L., Janes, K.A., Lin, K.Y., Wang, Y., August, J.T., Leong, K.W., Chitosan-DNA nanoparticles as gene carriers: Synthesis, characterization and transfection efficiency (2001) J Control Release, 70, pp. 399-421; Innes, N.P.T., Ogden, G.R., A technique for the study of endocytosis in human oral epithelial cells (1999) Arch Oral Biol, 44, pp. 519-523; O'Brien, J., Wilson, I., Orton, T., Pognan, F., Investigation of the Alamar Blue (resazurin) fluorescent dye for the assessment of mammalian cell cytotoxicity (2000) Eur J Biochem, 267, pp. 5421-5426; Ellman, G.L., Tissue sulfhydryl groups (1959) Arch Biochem Biophys, 82, pp. 70-77; Lee, D., Zhang, W., Shirley, S.A., Kong, X., Hellermann, G.R., Lockey, R.F., Mohapatra, S.S., Thiolated chitosan/DNA nanocomplexes exhibit enhanced and sustained gene delivery (2007) Pharm Res, 24, pp. 157-167; Loretz, B., Thaler, M., Bernkop-Schnurch, A., Role of sulfhydryl groups in transfection? A case study with chitosan-NAC nanoparticles (2007) Bioconjug Chem, 18, pp. 1028-1035; Deinhardt, K., Berninghausen, O., Willison, H.J., Hopkins, C.R., Schiavo, G., Tetanus toxin is internalized by a sequential clathrin-dependent mechanism initiated within lipid microdomains and independent of epsin 1 (2006) J Cell Biol, 174, pp. 459-471; Williamson, L.C., Neale, E.A., Bafilomycin A1 inhibits the action of tetanus toxin in spinal-cord neurons in cell-culture (1994) J Neurochem, 63, pp. 2342-2345; Bohnert, S., Schiavo, G., Tetanus toxin is transported in a novel neuronal compartment characterized by a specialized pH regulation (2005) J Biol Chem, 280, pp. 42336-42344
Keywords: animal cell; Animals; article; Binary complexes; Biodegradable polymers; Carbohydrate Conformation; Carbohydrate Sequence; Cations; Cell culture; Cell lines; cell population; Cells, Cultured; Chitin; chitosan; Complex surface; DNA; DNA complex; Dorsal root ganglia; Efficient systems; embryo; Ethylene; Ethylene Glycol; Female; Ganglia, Spinal; Gene delivery; gene delivery system; Gene delivery vectors; Gene therapy; Gene transfer; Gene Transfer Techniques; genetic transfection; Genetic Vectors; Grafting (chemical); Humans; imidazole; macrogol; materials testing; Mice; Molecular Sequence Data; Molecular Structure; mouse; Multicomponents; Nanocomplexes; Nanoparticle systems; nanoparticles; nerve cell culture; Neuron culture; Neuronal cell; NIH 3T3 Cells; nonhuman; Nontoxic fragment of tetanus toxin; Peripheral nervous system; Peripheral neuropathy; Polycations; Polyethylene Glycols; Polyethylene oxides; Pregnancy; Primary culture; rat; Rats; Rats, Wistar; spinal ganglion; Starting materials; Targeted; Tetanus toxin; Toxic materials; Transfection; Transfection efficiency

Chitosan/siRNA nanoparticles biofunctionalize nerve implants and enable neurite outgrowth - Mittnacht, U.; Hartmann, H.; Hein, S.; Oliveira, H.; Dong, M.; Pêgo, A.P.; Kjems, J.; Howard, K.A.; Schlosshauer, B. (Nano LettersNano Lett., 2010)
Microstructured 20 μm thick polymer filaments used as nerve implants were loaded with chitosan/siRNA nanoparticles to promote nerve regeneration and ensure local delivery of nanotherapeutics. The stable nanoparticles were rapidly internalized by cells and did not affect cell viability. Target mRNA was successfully reduced by 65-75% and neurite outgrowth was enhanced even in an inhibitory environment. This work, thus, supports the application of nanobiofunctionalized implants as a novel approach for spinal cord and nerve repair. © 2010 American Chemical Society.
Cited By (since 1996): 14Export Date: 21 November 2012Source: Scopusdoi: 10.1021/nl1016909Language of Original Document: EnglishCorrespondence Address: Schlosshauer, B.; NMI Natural and Medical Sciences Institute, University of Tübingen, Markwiesenstrasse 55, 72770 Reutlingen, Germany; email: schlosshauer@nmi.deChemicals/CAS: chitosan, 9012-76-4; Chitosan, 9012-76-4; RNA, Small Interfering; rhoA GTP-Binding Protein, 3.6.5.2References: Terzis, J.K., Skoulis, T.G., Soucacos, P.N., (1995) Int. Angiol., 14, pp. 264-77;Schmidt, C.E., Leach, J.B., (2003) Annu. Rev. Biomed. Eng., 5, pp. 293-347; Stokols, S., Tuszynski, M.H., (2004) Biomaterials, 25 (27), pp. 5839-46; Goraltchouk, A., Scanga, V., Morshead, C.M., Shoichet, M.S., (2006) J. Controlled Release, 110 (2), pp. 400-7; Wu, J., Chiu, D.T., (1999) Ann. Plast. Surg., 43, pp. 661-667; Chen, M.S., Huber, A.B., Van Der Haar, M.E., Frank, M., Schnell, L., Spillmann, A.A., Christ, F., Schwab, M.E., (2000) Nature, 403 (6768), pp. 434-9; Grandpre, T., Nakamura, F., Vartanian, T., Strittmatter, S.M., (2000) Nature, 403 (6768), pp. 439-44; Liu, B.P., Fournier, A., Grandpre, T., Strittmatter, S.M., (2002) Science, 297 (5584), pp. 1190-3; McKerracher, L., David, S., Jackson, D.L., Kottis, V., Dunn, R.J., Braun, P.E., (1994) Neuron, 13 (4), pp. 805-11; Mukhopadhyay, G., Doherty, P., Walsh, F.S., Crocker, P.R., Filbin, M.T., (1994) Neuron, 13 (3), pp. 757-67; Wang, K.C., Koprivica, V., Kim, J.A., Sivasankaran, R., Guo, Y., Neve, R.L., He, Z., (2002) Nature, 417 (6892), pp. 941-4; Mi, S., Lee, X., Shao, Z., Thill, G., Ji, B., Relton, J., Levesque, M., Pepinsky, R.B., (2004) Nat. Neurosci., 7 (3), pp. 221-8; Park, J.B., Yiu, G., Kaneko, S., Wang, J., Chang, J., He, X.L., Garcia, K.C., He, Z., (2005) Neuron, 45 (3), pp. 345-51; Shao, Z., Browning, J.L., Lee, X., Scott, M.L., Shulga-Morskaya, S., Allaire, N., Thill, G., Mi, S., (2005) Neuron, 45 (3), pp. 353-9; Wang, K.C., Kim, J.A., Sivasankaran, R., Segal, R., He, Z., (2002) Nature, 420 (6911), pp. 74-8; Wong, S.T., Henley, J.R., Kanning, K.C., Huang, K.H., Bothwell, M., Poo, M.M., (2002) Nat. Neurosci., 5 (12), pp. 1302-8; Elbashir, S.M., Harborth, J., Lendeckel, W., Yalcin, A., Weber, K., Tuschl, T., (2001) Nature, 411 (6836), pp. 494-8; Higuchi, H., Yamashita, T., Yoshikawa, H., Tohyama, M., (2003) Biochem. Biophys. Res. Commun., 301 (3), pp. 804-9; Fire, A., Xu, S., Montgomery, M.K., Kostas, S.A., Driver, S.E., Mello, C.C., (1998) Nature, 391 (6669), pp. 806-11; Tijsterman, M., Plasterk, R.H., (2004) Cell, 117 (1), pp. 1-3; De Fougerolles, A., Vornlocher, H.P., Maraganore, J., Lieberman, J., (2007) Nat. Rev. Drug Discovery, 6 (6), pp. 443-53; Shrivastava, N., Srivastava, A., (2008) Biotechnol. J., 3 (3), pp. 339-53; Soutschek, J., Akinc, A., Bramlage, B., Charisse, K., Constien, R., Donoghue, M., Elbashir, S., Vornlocher, H.P., (2004) Nature, 432 (7014), pp. 173-8; Takeshita, F., Ochiya, T., (2006) Cancer Sci., 97 (8), pp. 689-96; Bitko, V., Musiyenko, A., Shulyayeva, O., Barik, S., (2005) Nat. Med., 11 (1), pp. 50-5; Fjose, A., Drivenes, O., (2006) Birth Defects Res., C, 78 (2), pp. 150-71; Whitehead, K.A., Langer, R., Anderson, D.G., (2009) Nat. Rev. Drug Discovery, 8 (2), pp. 129-38; Liu, X., Howard, K.A., Dong, M., Andersen, M.O., Rahbek, U.L., Johnsen, M.G., Hansen, O.C., Kjems, J., (2007) Biomaterials, 28 (6), pp. 1280-8; Howard, K.A., Rahbek, U.L., Liu, X., Damgaard, C.K., Glud, S.Z., Andersen, M.O., Hovgaard, M.B., Kjems, J., (2006) Mol. Ther., 14 (4), pp. 476-84; Sell, S.A., McClure, M.J., Barnes, C.P., Knapp, D.C., Walpoth, B.H., Simpson, D.G., Bowlin, G.L., (2006) Biomed. Mater., 1 (2), pp. 72-80; Janes, K.A., Calvo, P., Alonso, M.J., (2001) Adv. Drug Delivery Rev., 47 (1), pp. 83-97; Pouton, C.W., Seymour, L.W., (2001) Adv. Drug Delivery Rev., 46 (1-3), pp. 187-203; Nel, A.E., Madler, L., Velegol, D., Xia, T., Hoek, E.M., Somasundaran, P., Klaessig, F., Thompson, M., (2009) Nat. Mater., 8 (7), pp. 543-57; Ishii, T., Okahata, Y., Sato, T., (2001) Biochim. Biophys. Acta, 1514 (1), pp. 51-64; Huang, M., Fong, C.W., Khor, E., Lim, L.Y., (2005) J. Controlled Release, 106 (3), pp. 391-406; Richardson, S.C., Kolbe, H.V., Duncan, R., (1999) Int. J. Pharm., 178 (2), pp. 231-43; Corsi, K., Chellat, F., Yahia, L., Fernandes, J.C., (2003) Biomaterials, 24 (7), pp. 1255-64; Moghimi, S.M., Symonds, P., Murray, J.C., Hunter, A.C., Debska, G., Szewczyk, A., (2005) Mol. Ther., 11 (6), pp. 990-5; Koping-Hoggard, M., Tubulekas, I., Guan, H., Edwards, K., Nilsson, M., Varum, K.M., Artursson, P., (2001) Gene Ther., 8 (14), pp. 1108-21; Moreira, C., Oliveira, H., Pires, L.R., Simoes, S., Barbosa, M.A., Pego, A.P., (2009) Acta Biomater., 5 (8), pp. 2995-3006; Lietz, M., Dreesmann, L., Hoss, M., Oberhoffner, S., Schlosshauer, B., (2006) Biomaterials, 27 (8), pp. 1425-36; Ribeiro-Resende, V.T., Koenig, B., Nichterwitz, S., Oberhoffner, S., Schlosshauer, B., (2009) Biomaterials, 30 (29), pp. 5251-9; Andersen, M.O., Howard, K.A., Paludan, S.R., Besenbacher, F., Kjems, J., (2008) Biomaterials, 29 (4), pp. 506-12; Anchordoquy, T.J., Allison, S.D., Molina, M.C., Girouard, L.G., Carson, T.K., (2001) Drug Discovery Today, 6 (9), pp. 463-470; Atala, A., Bauer, S.B., Soker, S., Yoo, J.J., Retik, A.B., (2006) Lancet, 367 (9518), pp. 1241-6; Lin, C.Y., Schek, R.M., Mistry, A.S., Shi, X., Mikos, A.G., Krebsbach, P.H., Hollister, S.J., (2005) Tissue Eng., 11 (9-10), pp. 1589-98; Suggate, E.L., Ahmed, Z., Read, M.L., Eaton-Charnock, K., Douglas, M.R., Gonzalez, A.M., Berry, M., Logan, A., (2009) Mol. Cell Neurosci., 40 (4), pp. 451-62; Ahmed, Z., Dent, R.G., Suggate, E.L., Barrett, L.B., Seabright, R.J., Berry, M., Logan, A., (2005) Mol. Cell Neurosci., 28 (3), pp. 509-23; Fournier, A.E., Takizawa, B.T., Strittmatter, S.M., (2003) J. Neurosci., 23 (4), pp. 1416-23
Keywords: animal; Animals; article; Cell Line; cell viability; chemistry; Chitin; chitosan; cytology; Drug delivery; genetic transfection; genetics; Local delivery; metabolism; Microstructured; nanobiofunctionalized implants; nanoparticle; nanoparticles; nerve cell; nerve regeneration; Nerve repair; neurite; Neurite outgrowth; Neurites; Neurons; Polymer filaments; Prostheses and Implants; prostheses and orthoses; rhoA GTP-Binding Protein; RhoA guanine nucleotide binding protein; RNA; RNA, Small Interfering; siRNA; small interfering RNA; Spinal cords; Transfection; ultrastructure

Comparison of a computer system evaluation of intrapartum cardiotocographic events and a consensus of clinicians. - Costa, M.A.; Ayres-de-Campos, D.; Machado, A.P.; Santos, C.C.; Bernardes, J. (Journal of perinatal medicineJ Perinat Med, 2010)
AIMS: To compare between computer analysis of intrapartum cardiotocography (CTG) features by the Omniview-SisPorto 3.5 and a consensus of clinicians. METHODS: Agreement study using 50 consecutively acquired tracings (206 h of signals) with >60 min duration, <10% signal loss and recorded in labor at term by internal fetal heart rate (FHR) monitoring. Tracings were divided into 10-min segments and independently analyzed by three experienced clinicians, in order to estimate the FHR baseline and identify periodic events. A consensus was reached using a three round Delphi procedure. Results were compared with the analysis provided by the Omniview-SisPorto 3.5 system. RESULTS: For baseline estimation, agreement between the computer and the consensus was high [intraclass correlation coefficient (ICC)=0.85; 95% confidence interval (CI) 0.46-0.93], with a mean difference of 3.7 bpm (limits of agreement -4.4-11.9 bpm), and 99% of differences under 15 bpm. A concordant identification was observed in 71% of accelerations (95% CI: 69%-73%), 68% of decelerations (95% CI: 66%-70%), and 87% of uterine contractions (95% CI: 85%-89%). CONCLUSIONS: A high agreement was observed between the Omniview-SisPorto 3.5 and a consensus of clinicians in evaluation of intrapartum CTG baseline, accelerations, decelerations and uterine contractions.
Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1515/JPM.2010.030PubMed ID: 20121542Language of Original Document: EnglishCorrespondence Address: Costa, M.A.email: cosantonia@gmail.com
Keywords: algorithm; Algorithms; article; Cardiotocography; comparative study; computer assisted diagnosis; Diagnosis, Computer-Assisted; Female; Fetal Heart; Fetal monitoring; fetus heart; fetus monitoring; human; Humans; instrumentation; methodology; physician; Physicians; physiology; Pregnancy

De novo expression of CD44 variants in sporadic and hereditary gastric cancer - Da Cunha, C.B.; Oliveira, C.; Wen, X.; Gomes, B.; Sousa, S.; Suriano, G.; Grellier, M.; Huntsman, D.G.; Carneiro, F.; Granja, P.L.; Seruca, R. (Laboratory InvestigationLab. Invest., 2010)
CD44 is the major ubiquitously expressed cell surface receptor for hyaluronate. The CD44 gene encodes several protein isoforms due to extensive alternative splicing and post-translational modifications. Some of these CD44 variable isoforms have been foreseen as key players in malignant transformation and their expression is highly restricted and highly specific, unlike the canonical CD44 standard isoform. In this study, we aimed at dissecting the mRNA splicing pattern of CD44 in normal stomach and gastric cancer (GC) cell lines (n9) using cloning and quantitative mRNA amplification assays. Moreover, we assessed the RNA levels and protein expression pattern of relevant splicing forms in distinct premalignant and malignant gastric lesions (sporadic (n43) and hereditary (n3) forms) using real-time RT-PCR and immunohistochemistry. We also explored the association of CD44 and E-cadherin expression by immunohistochemistry, as E-cadherin has a pivotal functional role in GC. We established the pattern of CD44 variant forms in normal stomach and gastric malignancy. We observed that although exon v6-containing isoforms were rarely expressed in normal gastric mucosa, they became increasingly expressed both in gastric premalignant (hyperplastic polyps, complete and incomplete intestinal metaplasia, low- and high-grade dysplasia) and malignant lesions (cell lines derived from GCs, primary sporadic GCs and hereditary diffuse GCs (HDGCs)). Moreover, we verified that whenever E-cadherin expression was absent, exon v6-containing CD44 isoforms were overexpressed. The lack of expression of CD44 isoforms containing exon v6 in the surface and foveolar epithelia of normal stomach and, its de novo expression in premalignant, as well as in sporadic and hereditary malignant lesions of the stomach, pinpoint CD44 v6-containg isoforms as potential biomarkers for early transformation of the gastric mucosa. Further, our results raise the hypothesis of using CD44v6 as a marker of early invasive intramucosal carcinoma in HDGC CDH1 mutation carriers that lack CDH1 expression in their tumors. © 2010 USCAP, Inc All rights reserved.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: LAINAdoi: 10.1038/labinvest.2010.155PubMed ID: 20856229Language of Original Document: EnglishCorrespondence Address: Da Cunha, C. B.; IPATIMUP, Institute of Molecular Pathology and Immunology, University of Porto, Rua Dr. Roberto Frias s/n, 4200-465 Porto, Portugal; email: rseruca@ipatimup.ptChemicals/CAS: uvomorulin, 112956-45-3; Antigens, CD44; CD44 protein, human; CD44v6 antigen; Cadherins; RNA, MessengerReferences: Aruffo, A., Stamenkovic, I., Melnick, M., CD44 is the principal cell surface receptor for hyaluronate (1990) Cell, 61, pp. 1303-1313;Screaton, G.R., Bell, M.V., Jackson, D.G., Genomic structure of DNA encoding the lymphocyte homing receptor CD44 reveals at least 12 alternatively spliced exons (1992) Proc Natl Acad Sci USA, 89, pp. 12160-12164; Ponta, H., Wainwright, D., Herrlich, P., Molecules in focus the CD44 protein family (1998) Int J Biochem Cell Biol, 30, pp. 299-305; Rudzki, Z., Jothy, S., CD44 and the adhesion of neoplastic cells (1997) Mol Pathol, 50, pp. 57-71; Shtivelman, E., Bishop, J.M., Expression of CD44 is repressed in neuroblastoma cells (1991) Mol Cell Biol, 11, pp. 5446-5453; De Marzo, A.M., Bradshaw, C., Sauvageot, J., CD44 and CD44v6 downregulation in clinical prostatic carcinoma: Relation to Gleason grade and cytoarchitecture (1998) Prostate, 34, pp. 162-168; Joensuu, H., Klemi, P.J., Toikkanen, S., Glycoprotein CD44 expression and its association with survival in breast cancer (1993) Am J Pathol, 143, pp. 867-874; Friedrichs, K., Kugler, G., Franke, F., CD44 isoforms in prognosis of breast cancer (1995) Lancet, 345, p. 1237; Kaufmann, M., Heider, K.H., Sinn, H.P., CD44 variant exon epitopes in primary breast cancer and length of survival (1995) Lancet, 345, pp. 615-619; Mulder, J.W., Kruyt, P.M., Sewnath, M., Colorectal cancer prognosis and expression of exon-v6-containing CD44 proteins (1994) Lancet, 344, pp. 1470-1472; Wielenga, V.J., Heider, K.H., Offerhaus, G.J., Expression of CD44 variant proteins in human colorectal cancer is related to tumor progression (1993) Cancer Res, 53, pp. 4754-4756; Terpe, H.J., Koopmann, R., Imhof, B.A., Expression of integrins and CD44 isoforms in non-Hodgkin's lymphomas: CD44 variant isoforms are preferentially expressed in high-grade malignant lymphomas (1994) J Pathol, 174, pp. 89-100; Takaishi, S., Okumura, T., Tu, S., Identification of gastric cancer stem cells using the cell surface marker CD44 (2009) Stem Cells, 27, pp. 1006-1020; Heider, K.-H., Dammrich, J., Skroch-Angel, P., Differential EXpression of CD44 splice variants in intestinal-and diffuse-type human gastric carcinomas and normal gastric mucosa (1993) Cancer Res, 53, pp. 4197-4203; Mayer, B., Jauch, K.W., Gunthert, U., De-novo expression of CD44 and survival in gastric cancer (1993) Lancet, 342, pp. 1019-1022; Muller, W., Schneiders, A., Heider, K.H., Expression and prognostic value of the CD44 splicing variants v5 and v6 in gastric cancer (1997) J Pathol, 183, pp. 222-227; Mirecka, J., Marx, D., Schauer, A., Immunohistochemical localization of CD44 variants 5 and 6 in human gastric mucosa and gastric cancer (1995) Anticancer Res, 15, pp. 1459-1465; Heider, K.H., Dammrich, J., Skroch-Angel, P., Differential expression of CD44 splice variants in intestinal-and diffuse-type human gastric carcinomas and normal gastric mucosa (1993) Cancer Res, 53, pp. 4197-4203; Hong, R.L., Lee, W.J., Shun, C.T., Expression of CD44 and its clinical implication in diffuse-type and intestinal-type gastric adenocarcinomas (1995) Oncology, 52, pp. 334-339; Ghaffarzadehgan, K., Jafarzadeh, M., Raziee, H.R., Expression of cell adhesion molecule CD44 in gastric adenocarcinoma and its prognostic importance (2008) World J Gastroenterol, 14, pp. 6376-6381; Carneiro, F., Huntsman, D.G., Smyrk, T.C., Model of the early development of diffuse gastric cancer in E-cadherin mutation carriers and its implications for patient screening (2004) J Pathol, 203, pp. 681-687; Suriano, G., Mulholland, D., De Wever, O., The intracellular E-cadherin germline mutation V832M lacks the ability to mediate cell-cell adhesion and to suppress invasion (2003) Oncogene, 22, pp. 5716-5719; Suriano, G., Oliveira, C., Ferreira, P., Identification of CDH1 germline missense mutations associated with functional inactivation of the E-cadherin protein in young gastric cancer probands (2003) Hum Mol Genet, 12, pp. 575-582; Suriano, G., Oliveira, M.J., Huntsman, D., E-cadherin germline missense mutations and cell phenotype: Evidence for the independence of cell invasion on the motile capabilities of the cells (2003) Hum Mol Genet, 12, pp. 3007-3016; Oliveira, C., Bordin, M.C., Grehan, N., Screening E-cadherin in gastric cancer families reveals germline mutations only in hereditary diffuse gastric cancer kindred (2002) Hum Mutat, 19, pp. 510-517; MacHado, J.C., Oliveira, C., Carvalho, R., E-cadherin gene (CDH1) promoter methylation as the second hit in sporadic diffuse gastric carcinoma (2001) Oncogene, 20, pp. 1525-1528; Huntsman, D.G., Carneiro, F., Lewis, F.R., Early gastric cancer in young, asymptomatic carriers of germ-line E-cadherin mutations (2001) N Engl J Med, 344, pp. 1904-1909; Carneiro, F., MacHado, J.C., Seruca, R., E-cadherin changes in gastric carcimona (1999) Histopathology, 35, pp. 477-478; Mateus, A.R., Simoes-Correia, J., Figueiredo, J., E-cadherin mutations and cell motility: A genotype-phenotype correlation (2009) Exp Cell Res, 315, pp. 1393-1402; Oliveira, C., Senz, J., Kaurah, P., Germline CDH1 deletions in hereditary diffuse gastric cancer families (2009) Hum Mol Genet, 18, pp. 1545-1555; Oliveira, C., Sousa, S., Pinheiro, H., Quantification of epigenetic and genetic second hits in CDH1 during hereditary diffuse gastric cancer syndrome progression (2009) Gastroenterology, 136, pp. 2137-2148; Lynch, H.T., Grady, W., Suriano, G., Gastric cancer: New genetic developments (2005) J Surg Oncol, 90, pp. 114-133. , discussion 133; Lauren, P., The two histological main types of gastric carcinoma: Diffuse and so-called intestinal-type carcinoma. An attempt at a histo-clinical classification (1965) Acta Pathol Microbiol Scand, 64, pp. 31-49; Filipe, M.I., Jass, J.R., Intestinal metaplasia subtypes and cancer risk (1986) Gastric Carcinoma, pp. 87-115. , Filipe MI, Jass JR (eds). Churchill Livingstone, London; Sato, S., Yokozaki, H., Yasui, W., Silencing of the CD44 gene by CpG methylation in a human gastric carcinoma cell line (1999) Jpn J Cancer Res, 90, pp. 485-489; Guilford, P.H.J., Harraway, J., McLeod, M., E-cadherin germline mutations in familial gastric cancer (1998) Nature, 26, p. 6674; Günthert, U., Hofmann, M., Rudy, W., A new variant of glycoprotein CD44 confers metastatic potential to rat carcinoma cells (1991) Cell, 65, pp. 13-24; Vr, O., Chen, L., Sleeman, J.P., CD44 is required for two consecutive steps in HGF/c-Met signaling (2002) Genes Dev, 16, pp. 3074-3086; Spk, D., Stefan, M., Wels, C., HGF-Promoted Motility in Primary Melanocytes Depends on CD44v6 Regulated via NF-kappa B, Egr-1, and C/EBP-beta (2010) J Investig Dermatol, 130, pp. 1893-1903; Mielgo, A., Van Driel, M., Bloem, A., A novel antiapoptotic mechanism based on interference of Fas signaling by CD44 variant isoforms (2006) Cell Death Differ, 13, pp. 465-477; Marhaba, R., Bourouba, M., Zoller, M., CD44v6 promotes proliferation by persisting activation of MAP kinases (2005) Cell Signal, 17, pp. 961-973; Bates, R.C., Edwards, N.S., Burns, G.F., A CD44 survival pathway triggers chemoresistance via lyn kinase and phosphoinositide 3-kinase/Akt in colon carcinoma cells (2001) Cancer Res, 61, pp. 5275-5283; Carvalho, R., Milne, A.N., Polak, M., A novel region of amplification at 11p12-13 in gastric cancer, revealed by representational difference analysis, is associated with overexpression of CD44v6, especially in early-onset gastric carcinomas (2006) Genes Chromosomes Cancer, 45, pp. 967-975; Heider, K.H., Hofmann, M., Hors, E., A human homologue of the rat metastasis-associated variant of CD44 is expressed in colorectal carcinomas and adenomatous polyps (1993) J Cell Biol, 120, pp. 227-233; Gulmann, C., Grace, A., Leader, M., CD44v6: A potential marker of malignant transformation in intestinal metaplasia of the stomach? An immunohistochemical study using tissue microarrays (2003) Eur J Gastroenterol Hepatol, 15, pp. 981-986; Wimmel, A., Kogan, E., Ramaswamy, A., Variant expression of CD44 in preneoplastic lesions of the lung (2001) Cancer, 92, pp. 1231-1236; Afify, A.M., Craig, S., Paulino, A.F., Expression of hyaluronic acid and its receptors, CD44s and CD44v6, in normal, hyperplastic, and neoplastic endometrium (2005) Ann Diagn Pathol, 9, pp. 312-318; Soon Cheol, H., Jae Yun, S., Jae Kwan, L., Significance of CD44v6 expression in gynecologic malignancies (2006) J Obstet Gynaecol Res, 32, pp. 379-386; Afify, A., Ma, M., Braggin, J., Expression of CD44s, CD44v6, and hyaluronan across the spectrum of normal-hyperplasia-carcinoma in breast (2008) Appl Immunohistochem Mol Morphol, 16, pp. 121-127; Judd, L.M., Andriga, A., Rubio, C.A., Gastric achlorhydria in H/K-ATPase-deficient (Atp4a(-/-)) mice causes severe hyperplasia, muco-cystic metaplasia and upregulation of growth factors (2005) J Gastroenterol Hepatol, 20, pp. 1266-1278; Liu, Y.J., Yan, P.S., Li, J., Expression and significance of CD44 s, CD44v6, and nm23 mRNA in human cancer (2005) World J Gastroenterol, 11, pp. 6601-6606; Polkowski, W.P., Skomra, D.G., Mielko, J., E-cadherin expression as predictive marker of proximal resection line involvement for advanced carcinoma of the gastric cardia (2004) E J Surg Oncol, 30, pp. 1084-1092; Seiter, S.A.R., Reber, S., Komitowski, D., Prevention of tumor metastasis formation by anti-variant CD44 (1993) J Experiment Med, 177, pp. 443-455; Reeder, J.A., Gotley, D.C., Walsh, M.D., Expression of ANTisense CD44 variant 6 inhibits colorectal tumor metastasis and tumor growth in a wound environment (1998) Cancer Res, 58, pp. 3719-3726; Nishii, T., Yashiro, M., Shinto, O., Cancer stem cell-like SP cells have a high adhesion ability to the peritoneum in gastric carcinoma (2009) Cancer Sci, 100, pp. 1397-1402; Carneiro, F., Huntsman, D.G., Smyrk, T.C., Model of the early development of diffuse gastric cancer in E-cadherin mutation carriers and its implications for patient screening (2004) J Pathol, 203, pp. 681-687; Pdp, P., Guilford, P., Caldas, C., The International Gastric Cancer Linkage C. Incidence of gastric cancer and breast cancer in CDH1 (E-cadherin) mutation carriers from hereditary diffuse gastric cancer families (2001) Gastroenterology, 121, pp. 1348-1353; Humar, B., Fukuzawa, R., Blair, V., Destabilized adhesion in the gastric proliferative zone and c-Src kinase activation mark the development of early diffuse gastric cancer (2007) Cancer Res, 67, pp. 2480-2489; Ferrari, M., Cancer nanotechnology: Opportunities and challenges (2005) Nat Rev Cancer, 5, pp. 161-171; Yww, W., Chen, Y., Huang, K., The investigation of polymer-siRNA nanoparticle for gene therapy of gastric cancer in vitro (2010) Int J Nanomed, 5, pp. 129-136
Keywords: Alternative Splicing; Antigens, CD44; article; Cadherins; CD44; CD44v6; CD44v6 antigen; CD44v7 antigen; Cell Line, Tumor; clinical article; controlled study; E-cadherin; familial cancer; Gastric Mucosa; Germ-Line Mutation; HDGC; Hermes antigen; human; human tissue; Humans; immunohistochemistry; intestine metaplasia; messenger RNA; Neoplasm Metastasis; priority journal; protein expression; real time polymerase chain reaction; reverse transcription polymerase chain reaction; RNA splicing; RNA, Messenger; splicing; sporadic GC; stomach; stomach cancer; stomach mucosa; Stomach Neoplasms; stomach polyp; tumor marker; unclassified drug; uvomorulin

Effect of nanoscale topography on fibronectin adsorption, focal adhesion size and matrix organisation - González-García, C.; Sousa, S.R.; Moratal, D.; Rico, P.; Salmerón-Sánchez, M. (Colloids and Surfaces B: BiointerfacesColloids Surf. B Biointerfaces, 2010)
Phase separation of PLLA/PS (50/50, w/w) solutions during a spin-casting process gives rise to well-defined nanotopographies of 14, 29 and 45. nm deep pits depending on the concentration of the solution. Their influence on the biological activity of fibronectin (FN) was investigated. FN adsorption was quantified by radiolabelling the protein. The amount of adsorbed FN was higher on the 14. nm deep pit nanotopography than on the other two surfaces. FN distribution between valleys and peaks was investigated by AFM combined with image analysis. FN tends to adsorb preferentially on the valleys of the nanotopography only for the 14. nm system and when adsorbed from solutions of concentration lower than 10μg/ml. Higher concentration of the FN solution leads to evenly distribution of the protein throughout the surface; moreover, there is no difference in the distribution of the protein between valleys and peaks for the other two systems (29 and 45. nm) irrespective of the concentration of the FN solution. The biological activity of the adsorbed protein layer was assessed by investigating MC3T3 osteoblast-like cells adhesion, FN reorganisation and late matrix formation on the different substrates. Even if initial cell adhesion is excellent for every substrate, the size of the focal adhesion plaques increases as the size of the pits in the nanotopography does. This is correlated to FN reorganisation, which only takes places on the 29 and 45. nm deep pits surfaces, where enhanced late matrix production was also found. © 2010 Elsevier B.V.
Cited By (since 1996): 25Export Date: 21 November 2012Source: ScopusCODEN: CSBBEdoi: 10.1016/j.colsurfb.2010.01.021PubMed ID: 20185279Language of Original Document: EnglishCorrespondence Address: Rico, P.; Center for Biomaterials and Tissue Engineering, Universidad Politécnica de Valencia, 46022 Valencia, Spain; email: parico@upvnet.upv.esChemicals/CAS: fibronectin, 86088-83-7; polylactic acid, 26100-51-6; polystyrene, 9003-53-6; Fibronectins; ProteinsReferences: Spie, J., (2002) Ann. N. Y. Acad. Sci., 961, p. 1;Griffin, L., Naughton, G., (2002) Science, 259, p. 1009; Grinnell, F., (1986) J. Cell Biol., 103, p. 2697; Hynes, R.O., (2002) Cell, 110, p. 673; Wong, J.Y., Leach, J.B., Brown, X.Q., (2004) Surf. Sci., 570, p. 119; Schwarz, U.S., Bischofs, I.B., (2005) Med. Eng. Phys., 27, p. 763; Ohara, P.T., Buck, R.C., (1979) Exp. Cell Res., 121, p. 235; Lim, J.Y., Donahue, H.J., (2007) Tissue Eng., 13, p. 1879; Affrossman, S., Jerome, R., O'Neill, S.A., Schmitt, T., Stamm, M., (2000) Colloid Polym. Sci., 278, p. 888; Denis, F.A., Hanarp, P., Sutherland, D.S., Dufrene, Y.F., (2002) Nanoletters, 2, p. 1419; Vieu, C., Carcenac, F., Pepin, A., Chen, Y., Mejias, M., Lebib, A., Manin-Ferlazzo, L., Launois, H., (2000) Appl. Surf. Sci., 164, p. 111; Kriparamanan, R., Aswath, P., Zhou, A., Tang, L., Nguyen, K.T., (2006) J. Nanosci. Nanotechnol., 6, p. 1905; Dalby, M.J., Giannaras, D., Riehle, M.O., Gadegaard, N., Affrossman, S., Curtis, A.S.G., (2004) Biomaterials, 25, p. 77; Lim, J.Y., Dreiss, D., Zhou, Z., Hansen, J.C., Siedlecki, C.A., Hengstebeck, R.W., Cheng, J., Donahue, H.J., (2007) Biomaterials, 28, p. 1787; Dalby, M.J., Hart, A., Yarwood, S.J., (2008) Biomaterials, 29, p. 282; Zinger, O., Zhao, G., Schwartz, Z., Simpson, J., Wieland, M., Landlolt, D., Boyan, B., (2005) Biomaterials, 26, p. 1837; Dalby, M.J., Gadegaard, N., Tare, R., Andar, A., Riehle, M.O., Herzyk, P., Wilkinson, C.D.W., Oreffo, R.O.C., (2007) Nat. Mater., 9, p. 997; Dalby, M.J., McCloy, D., Robertson, M., Wilkinson, C.D.W., Oreffo, R.O.C., (2006) Biomaterials, 27, p. 1306; Pirouz-Dolatshahi, A., Rechendorff, K., Hovgaard, M.B., Foss, M., Chevallier, J., Besenbacher, F., (2008) Colloid Surf. B, 66, p. 53; Khor, H.L., Kukula, H., Tamada, K., Knoll, W., Moeller, M., Hutmacher, D.W., (2007) Biomacromolecules, 8, p. 1530; Cai, K., Bossert, J., Jandt, K., (2006) Colloid Surf. B, 49, p. 136; (1993), p. 64. , Iodine-125, Amersham International, Little Chalfont, Buckinghamshire, U.K.Sousa, S.R., Brás, M., Moradas-Ferreira, P., Barbosa, M.A., (2007) Langmuir, 23, p. 7046; Otsu, N.A., (1979) IEEE Trans. Syst. Man Cybern., 9, p. 62; Gonzalez, R.C., Woods, R.E., Eddins, S.L., (2003) Digital Image Processing Using MATLAB, , Prentice-Hall, Upper Saddle River, NJ; Gonzalez, R.C., Woods, R.E., (2007) Digital Image Processing, , Prentice-Hall, Upper Saddle River, NJ; (2006), MATLAB Image Processing Toolbox User's Guide, The MathWorks, Inc., Natick, MAAllen, L.T., Tosetto, M., Miller, I.S., O'Connor, D.P., Penney, S.C., Lynch, I., Keenan, A.K., Gallagher, W.M., (2006) Biomaterials, 27, p. 3096; Gugutkov, D., Altankov, G., Rodríguez Hernández, J.C., Monleón Pradas, M., Salmerón Sánchez, M., (2010) J. Biomed. Mater. Res. A, 92, p. 322; Rico, P., Rodríguez Hernández, J.C., Moratal, D., Monleón Pradas, M., Salmerón Sánchez, M., (2009) Macromol. Biosci., 9, p. 766; Keselowsky, B.G., Collard, D.M., García, A.J., (2003) J. Biomed. Mater. Res. A, 66, p. 247; Lee, M.H., Ducheyne, P., Lynch, L., Boettiger, D., Composto, R.J., (2006) Biomaterials, 27, p. 1907; Costa Martínez, E., Rodríguez Hernández, J.C., Machado, M., Mano, J., Gómez Ribelles, J.L., Monleón Pradas, M., Salmerón Sánchez, M., (2008) Tissue Eng., 14, p. 1751; Lim, J.Y., Hansen, J.C., Siedlecki, C.A., Hengstebeck, R.A., Cheng, J., Winograd, N., (2005) Biomacromolecules, 6, p. 3319; Liu, X., Lim, J.Y., Donahue, H.J., Dhurjati, R., Maestro, A.M., Vogler, E.A., (2007) Biomaterials, 28, p. 4535; Dalby, M.J., Yarwood, S.J., Riehle, M.O., Johnstone, H.J., Affressman, S., Curtis, A.S., (2002) Exp. Cell Res., 276, p. 1; Dalby, M.J., Childs, S., Riehle, M.O., Johnston, H.J.H., Affrossman, S., (2003) Biomaterials, 24, p. 927; Dalby, M.J., McCloy, D., Robertson, M., Agheli, H., Sutherland, D., Affrossman, S., Oreffo, R.O.C., (2006) Biomaterials, 27, p. 2980; Dalby, M.J., (2005) Med. Eng. Phys., 27, p. 730; Galbraith, C.G., Yamada, K.M., Sheetz, M.P., (2002) J. Cell Biol., 159, p. 695; Balaban, N.Q., Schwarz, U.S., Riveline, D., Goichberg, P., Tzur, G., Sabanay, I., (2001) Nat. Cell Biol., 3, p. 466; Pegueroles, M., Aparicio, C., Bosio, M., Engel, E., Gil, F.J., Planell, J.A., Altankov, G., Acta Biomater. (). doi:10.1016/j.actbio.2009.07.030Altankov, G., Groth, T., (1994) J. Mater. Sci. Mater. Med., 5, p. 732; Altankov, G., Groth, T., (1996) J. Mater. Sci. Mater. Med., 7, p. 425; Altankov, G., Grinnell, F., Groth, T., (1996) J. Biomed. Mater. Res., 30, p. 385; Tzoneva, R., Groth, T., Altankov, G., Paul, D., (2002) J. Mater. Sci. Mater. Med., 13, p. 1235; Gonçalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., (2005) Biomaterials, 26, p. 3891; Luthen, F., Lange, R., Becker, P., Rychly, J., Beck, U., Nebe, J.G.B., (2005) Biomaterials, 26, p. 2423; Geiger, B., Bershadsky, A., Pankov, R., Yamada, K.M., (2001) Nat. Rev. Mol. Cell Biol., 2, p. 793; Altankov, G., Groth, T., (1996) J. Biomater. Sci. Polym. Ed., 8, p. 299
Keywords: 3T3 Cells; Adhesion; Adsorption; AFM; animal cell; Animals; article; Atomic force microscopy; Bioactivity; Biological activities; biological activity; Casting process; cell adhesion; Cell Line; concentration (parameters); Concentration (process); Concentration of; Deep pit; Different substrates; Electric currents; extracellular matrix; Fibronectin; Fibronectin adsorption; Fibronectins; focal adhesion; Focal adhesion plaques; Focal adhesions; Humans; Image analysis; Image Processing, Computer-Assisted; isotope labeling; Landforms; matrix; Matrix formation; Mice; Microscopy, Atomic Force; nanomaterial; Nanoscale topography; Nanotechnology; Nanotopographies; Nanotopography; nonhuman; osteoblast; Osteoblast-like cells; Osteoblasts; Phase separation; polylactic acid; polystyrene; priority journal; Protein adsorption; Protein layers; protein localization; Proteins; Radiolabelling; Reorganisation; Substrates; Surface Properties

Functionalization of poly(amidoamine) dendrimers with hydrophobic chains for improved gene delivery in mesenchymal stem cells - Santos, J.L.; Oliveira, H.; Pandita, D.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (Journal of Controlled ReleaseJ. Control. Release, 2010)
A new family of gene delivery vectors is synthesized consisting of a medium-size generation PAMAM dendrimer (generation 5, with amine termini) core randomly linked at the periphery to hydrophobic chains that vary in length (12 to 16 carbon alkyl chains) and number (from 4.2 to 9.7 in average). The idea subjacent to the present work is to join the advantages of the cationic nature of the dendrimer with the capacity of lipids to interact with biological membranes. Unlike other amphiphilic systems designed for the same purpose, where the hydrophobic and hydrophilic moieties coexist in opposite sides, the present vectors have a hydrophilic interior and a hydrophobic corona. The vectors are characterized in respect to their ability to neutralize, bind and compact plasmid DNA (pDNA). The complexes formed between the vectors and pDNA are analyzed concerning their size, ζ-potential, resistance to serum nucleases, capacity of being internalized by cells and transfection efficiency. These new vectors show a remarkable capacity for mediating the internalization of pDNA with minimum cytotoxicity, being this effect positively correlated with the -CH 2- content present in the hydrophobic corona. Gene expression in MSCs, a cell type with relevancy in the regenerative medicine clinical context, is also enhanced using the new vectors but, in this case, the higher efficiency is shown by the vectors containing the smallest hydrophobic chains. © 2010 Elsevier B.V.
Cited By (since 1996): 28Export Date: 21 November 2012Source: ScopusCODEN: JCREEdoi: 10.1016/j.jconrel.2010.01.034PubMed ID: 20138937Language of Original Document: EnglishCorrespondence Address: Tomás, H.; CQM - Centro de Química da Madeira, MMRG, Departamento de Química, Universidade da Madeira, Campus Universitário da Penteada, 9000-390 Funchal, Portugal; email: lenat@uma.ptChemicals/CAS: lipid, 66455-18-3; nuclease, 9026-81-7; Cations; DNA, 9007-49-2; Dendrimers; Lipids; PAMAM StarburstReferences: Segura, T., Shea, L.D., Materials for non-viral gene delivery (2001) Annu. Rev. Mat. Res., 31, pp. 25-46;Mastrobattista, E., Bravo, S.A., van der Aa, M., Crommelin, D.J.A., Nonviral gene delivery systems: from simple transfection agents to artificial viruses (2005) Drug Discov. Today Technol., 2, pp. 103-109; Colella, P., Cotugno, G., Auricchio, A., Ocular gene therapy: current progress and future prospects (2009) Trends Mol. Med., 15, pp. 23-31; Scanlon, K.J., Cancer gene therapy: challenges and opportunities (2004) Anticancer Res., 24, pp. 501-504; Gersbach, C.A., Phillips, J.E., Garcia, A.J., Genetic engineering for skeletal regenerative medicine (2007) Annu. Rev. Biomed. Eng., 9, pp. 87-119; Heyde, M., Partridge, K.A., Oreffo, R.O., Howdle, S.M., Shakesheff, K.M., Garnett, M.C., Gene therapy used for tissue engineering applications (2007) J. Pharm. Pharmacol., 59, pp. 329-350; Gafni, Y., Turgeman, G., Liebergal, M., Pelled, G., Gazit, Z., Gazit, D., Stem cells as vehicles for orthopedic gene therapy (2004) Gene Ther., 11, pp. 417-426; Vaananen, H.K., Mesenchymal stem cells (2005) Ann. Med., 37, pp. 469-479; Phillips, J.E., Gersbach, C.A., Garcia, A.J., Virus-based gene therapy strategies for bone regeneration (2007) Biomaterials, 28, pp. 211-229; Lundstrom, K., Latest development in viral vectors for gene therapy (2003) Trends Biotechnol., 21, pp. 117-122; Noel, D., Gazit, D., Bouquet, C., Apparailly, F., Bony, C., Plence, P., Millet, V., Jorgensen, C., Short-term BMP-2 expression is sufficient for in vivo osteochondral differentiation of mesenchymal stem cells (2004) Stem Cells, 22, pp. 74-85; Mintzer, M.A., Simanek, E.E., Nonviral vectors for gene delivery (2009) Chem. Rev., 109, pp. 259-302; Hamm, A., Krott, N., Breibach, I., Blindt, R., Bosserhoff, A.K., Efficient transfection method for primary cells (2002) Tissue Eng., 8, pp. 235-245; McMahon, J.M., Conroy, S., Lyons, M., Greiser, U., O'Shea, C., Strappe, P., Howard, L., O'Brien, T., Gene transfer into rat mesenchymal stem cells: a comparative study of viral and nonviral vectors (2006) Stem Cells Dev., 15, pp. 87-96; Jang, W.-D., Selim, K.M.K., Lee, C.-H., Kang, I.-K., Bioinspired application of dendrimers: from bio-mimicry to biomedical applications (2009) Prog. Polym. Sci., 34, pp. 1-23; Svenson, S., Tomalia, D.A., Dendrimers in biomedical applications-reflections on the field (2005) Adv. Drug Deliv. Rev., 57, pp. 2106-2129; Caminade, A.M., Turrin, C.O., Majoral, J.P., Dendrimers and DNA: combinations of two special topologies for nanomaterials and biology (2008) Chemistry, 14, pp. 7422-7432; Dufes, C., Uchegbu, I.F., Schatzlein, A.G., Dendrimers in gene delivery (2005) Adv. Drug Deliv. Rev., 57, pp. 2177-2202; Guillot, M., Eisler, S., Diederich, F., Dendritic vectors for gene transfection (2007) New J. Chem., 31, pp. 1111-1127; Lechardeur, D., Verkman, A.S., Lukacs, G.L., Intracellular routing of plasmid DNA during non-viral gene transfer (2005) Adv. Drug Deliv. Rev., 57, pp. 755-767; Smith, D.K., Dendrimers and the double helix - from DNA binding towards gene therapy (2008) Curr. Top. Med. Chem., 8, pp. 1187-1203; Dobrovolskaia, M.A., McNeil, S.E., Immunological properties of engineered nanomaterials (2007) Nat. Nanotechnol., 2, pp. 469-478; Kukowska-Latallo, J.F., Bielinska, A.U., Johnson, J., Spindler, R., Tomalia, D.A., Baker, J.R., Efficient transfer of genetic material into mammalian cells using Starburst polyamidoamine dendrimers (1996) Proc. Natl. Acad. Sci. U.S.A., 93, pp. 4897-4902; Santos, J.L., Oramas, E., Pego, A.P., Granja, P.L., Tomas, H., Osteogenic differentiation of mesenchymal stem cells using PAMAM dendrimers as gene delivery vectors (2009) J. Control. Release, 134, pp. 141-148; Dennig, J., Duncan, E., Gene transfer into eukaryotic cells using activated polyamidoamine dendrimers (2002) J. Biotechnol., 90, pp. 339-347; Kono, K., Akiyama, H., Takahashi, T., Takagishi, T., Harada, A., Transfection activity of polyamidoamine dendrimers having hydrophobic amino acid residues in the periphery (2005) Bioconjug. Chem., 16, pp. 208-214; Takahashi, T., Harada, A., Emi, N., Kono, K., Preparation of efficient gene carriers using a polyamidoamine dendron-bearing lipid: improvement of serum resistance (2005) Bioconjug. Chem., 16, pp. 1160-1165; Takahashi, T., Kojima, C., Harada, A., Kono, K., Alkyl chain moieties of polyamidoamine dendron-bearing lipids influence their function as a nonviral gene vector (2007) Bioconjug. Chem., 18, pp. 1349-1354; Takahashi, T., Kono, K., Itoh, T., Emi, N., Takagishi, T., Synthesis of novel cationic lipids having polyamidoamine dendrons and their transfection activity (2003) Bioconjug. Chem., 14, pp. 764-773; Jones, S.P., Gabrielson, N.P., Pack, D.W., Smith, D.K., Synergistic effects in gene delivery - a structure-activity approach to the optimisation of hybrid dendritic-lipidic transfection agents (2008) Chem. Commun., 39, pp. 4700-4702; Shah, D.S., Sakthivel, T., Toth, I., Florence, A.T., Wilderspin, A.F., DNA transfection and transfected cell viability using amphipathic asymmetric dendrimers (2000) Int. J. Pharm., 208, pp. 41-48; Ahmad, A., Evans, H.M., Ewert, K., George, C.X., Samuel, C.E., Safinya, C.R., New multivalent cationic lipids reveal bell curve for transfection efficiency versus membrane charge density: lipid-DNA complexes for gene delivery (2005) J. Gene Med., 7, pp. 739-748; Ewert, K.K., Evans, H.M., Zidovska, A., Bouxsein, N.F., Ahmad, A., Safinya, C.R., A columnar phase of dendritic lipid-based cationic liposome-DNA complexes for gene delivery: hexagonally ordered cylindrical micelles embedded in a DNA honeycomb lattice (2006) J. Am. Chem. Soc., 128, pp. 3998-4006; Guillot, M., Eisler, S., Weller, K., Merkle, H.P., Gallani, J.L., Diederich, F., Effects of structural modification on gene transfection and self-assembling properties of amphiphilic dendrimers (2006) Org. Biomol. Chem., 4, pp. 766-769; Joester, D., Losson, M., Pugin, R., Heinzelmann, H., Walter, E., Merkle, H.P., Diederich, F., Amphiphilic dendrimers: novel self-assembling vectors for efficient gene delivery (2003) Angew. Chem. Int. Ed., 42, pp. 1486-1490; Alvarez, E., Girones, N., Davis, R.J., Inhibition of the receptor-mediated endocytosis of diferric transferrin is associated with the covalent modification of the transferrin receptor with palmitic acid (1990) J. Biol. Chem., 265, pp. 16644-16655; Jevprasesphant, R., Penny, J., Attwood, D., McKeown, N.B., D'Emanuele, A., Engineering of dendrimer surfaces to enhance transepithelial transport and reduce cytotoxicity (2003) Pharm. Res., 20, pp. 1543-1550; Snyder, S.L., Sobocinski, P.Z., An improved 2,4,6-trinitrobenzenesulfonic acid method for the determination of amines (1975) Anal. Biochem., 64, pp. 284-288; Lapidot, Y., Rappoport, S., Wolman, Y., Use of esters of N-hydroxysuccinimide in the synthesis of N-acylamino acids (1967) J. Lipid. Res., 8, pp. 142-145; Gao, X., Huang, L., Potentiation of cationic liposome-mediated gene delivery by polycations (1996) Biochemistry, 35, pp. 1027-1036; Aubin, J.E., Osteoprogenitor cell frequency in rat bone marrow stromal populations: role for heterotypic cell-cell interactions in osteoblast differentiation (1999) J. Cell Biochem., 72, pp. 396-410; Perrot, S., Dutertre-Catella, H., Martin, C., Rat, P., Warnet, J.M., Resazurin metabolism assay is a new sensitive alternative test in isolated pig cornea (2003) Toxicol. Sci., 72, pp. 122-129; Hosseinkhani, H., Yamamoto, M., Inatsugu, Y., Hiraoka, Y., Inoue, S., Shimokawa, H., Tabata, Y., Enhanced ectopic bone formation using a combination of plasmid DNA impregnation into 3-D scaffold and bioreactor perfusion culture (2006) Biomaterials, 27, pp. 1387-1398; Wong, S.Y., Pelet, J.M., Putnam, D., Polymer systems for gene delivery - past, present, and future (2007) Prog. Polym. Sci., 32, pp. 799-837; Abbasi, M., Uludag, H., Incani, V., Hsu, C.Y., Jeffery, A., Further investigation of lipid-substituted poly(L-lysine) polymers for transfection of human skin fibroblasts (2008) Biomacromolecules, 9, pp. 1618-1630; Sorgi, F.L., Bhattacharya, S., Huang, L., Protamine sulfate enhances lipid-mediated gene transfer (1997) Gene Ther., 4, pp. 961-968; Lampela, P., Soininen, P., Urtti, A., Männistö, P.T., Raasmaja, A., Synergism in gene delivery by small PEIs and three different nonviral vectors (2004) Int. J. Pharm., 270, pp. 175-184; Brito, L., Little, S., Langer, R., Amiji, M., Poly(β-amino ester) and cationic phospholipid-based lipopolyplexes for gene delivery and transfection in human aortic endothelial and smooth muscle cells (2008) Biomacromolecules, 9, pp. 1179-1187; Hardy, J.G., Love, C.S., Gabrielson, N.P., Pack, D.W., Smith, D.K., Synergistic effects on gene delivery - co-formulation of small disulfide-linked dendritic polycations with Lipofectamine 2000TM (2009) Org. Biomol. Chem., 7, pp. 789-793; Callow, P., Fragneto, G., Cubitt, R., Barlow, D.J., Lawrence, M.J., Timmins, P., Interaction of cationic lipid vesicles with model cell membranes - as determined by neutron reflectivity (2005) Langmuir, 21, pp. 7912-7920; Malik, N., Wiwattanapatapee, R., Klopsch, R., Lorenz, K., Frey, H., Weener, J.W., Meijer, E.W., Duncan, R., Dendrimers: relationship between structure and biocompatibility in vitro, and preliminary studies on the biodistribution of 125I-labelled polyamidoamine dendrimers in vivo (2000) J. Control. Release, 65, pp. 133-148
Keywords: amphophile; animal cell; animal experiment; article; Biological membranes; Biomedical applications; cation; Cations; Cell culture; cell membrane transport; cell type; Cellular uptake; controlled study; Cytotoxicity; dendrimer; Dendrimers; DNA; DNA binding; Dyes; Functional polymers; Gene delivery; gene delivery system; gene expression; Gene therapy; Gene transfer; Gene Transfer Techniques; gene vector; Genes; genetic transfection; Genetic Vectors; Humans; Hydrocarbons; hydrophilicity; hydrophobicity; internalization; lipid; Lipids; male; Mesenchymal stem cell; Mesenchymal Stem Cells; nonhuman; nuclease; Nucleic acids; plasmid DNA; Plasmids; Poly(amidoamine) dendrimers; polyamidoamine; Polyamidoamine dendrimers; priority journal; rat; Regenerative Medicine; Stem cells; Transfection; Vectors; Zeta potential

Immobilization of human mesenchymal stem cells within RGD-grafted alginate microspheres and assessment of their angiogenic potential - Bidarra, S.J.; Barrias, C.C.; Barbosa, M.A.; Soares, R.; Granja, P.L. (BiomacromoleculesBiomacromolecules, 2010)
In this work, human mesenchymal stem cells (hMSC) immobilized in RGD-coupled alginate microspheres, with a binary composition of high and low molecular weight alginate, were investigated. Cells immobilized within RGD-alginate microspheres (during 21 days) showed metabolic activity, with an overall viability higher than 90%, short cell extensions, and, when induced, they were able to differentiate into the osteogenic lineage. In osteogenic conditions (comparing to basal conditions), immobilized cells presented alkaline phosphatase (ALP) activity and an upregulation of ALP, collagen type I, and Runx 2 expression. Moreover, mineralization was also detected in immobilized cells under osteogenic stimulus. In addition, it was demonstrated for the first time that MSCs immobilized in this 3D matrix were able to enhance the ability of neighboring endothelial cells to form tubelike structures. Overall, these findings represent a step forward in the development of injectable stem cell carriers for bone tissue engineering. © 2010 American Chemical Society.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm100264aPubMed ID: 20690708Language of Original Document: EnglishCorrespondence Address: Granja, P. L.; INEB-Instituto de Engenharia Biomédica, Rua do Campo Alegre No. 823, 4150-180 Porto, Portugal; email: pgranja@ineb.up.ptMolecular Sequence Numbers: GENBANK: BC021289, NM_000088, NM_002046;Chemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; alkaline phosphatase, 9001-78-9; arginylglycylaspartic acid, 99896-85-2; Alginates; Alkaline Phosphatase, 3.1.3.1; Collagen Type I; DNA Primers; Oligopeptides; arginyl-glycyl-aspartic acid, 99896-85-2References: Temenoff, J.S., Mikos, A.G., Injectable biodegradable materials for orthopedic tissue engineering (2000) Biomaterials, 21, pp. 2405-2412;Barralet, J.E., Wang, L., Lawson, M., Triffitt, J.T., Cooper, P.R., Shelton, R.M., Comparison of bone marrow cell growth on 2D and 3D alginate hydrogels (2005) J. Mater. Sci.: Mater. Med., 16, pp. 515-519; Ma, H.L., Hung, S.C., Lin, S.Y., Chen, Y.L., Lo, W.H., Chondrogenesis of human mesenchymal stem cells encapsulated in alginate beads (2003) J. Biomed. Mater. Res., 64, pp. 273-281; Augst, A.D., Kong, H.J., Mooney, D.J., Alginate hydrogels as biomaterials (2006) Macromol. Biosci., 6, pp. 623-633; Smidsrod, O., Skjak-Braek, G., Alginate as immobilization matrix for cells (1990) Trends Biotechnol., 8, pp. 71-78; Jen, A.C., Wake, M.C., Mikos, A.G., Review: Hydrogels for cell immobilization (1996) Biotechnol. Bioeng., 50, pp. 357-364; Oliveira, S.M., Barrias, C.C., Almeida, I.F., Costa, P.C., Ferreira, M.R.P., Bahia, M.F., Barbosa R. M, A., Injectability of a bone filler system based on hydroxyapatite microspheres and a vehicle with in situ gel-forming ability (2008) J. Biomed. Mater. Res. B, 87, pp. 49-8; Evangelista, M.B., Hsiong, S.X., Fernandes, R., Sampaio, P., Kong, H.-J., Barrias, C.C., Salema, R., Granja, P.L., Upregulation of bone cell differentiation through immobilization within a synthetic extracellular matrix (2007) Biomaterials, 28, pp. 3644-3655; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20, pp. 45-53; Kong, H.J., Smith, M.K., Mooney, D.J., Designing alginate hydrogels to maintain viability of immobilized cells (2003) Biomaterials, 24, pp. 4023-4029; Grellier, M., Granja, P.L., Fricain, J.-C., Bidarra, S.J., Renard, M., Bareille, R., Bourget, C., Barbosa, M.A., The effect of the co-immobilization of human osteoprogenitors and endothelial cells within alginate microspheres on mineralization in a bone defect (2009) Biomaterials, 30, pp. 3271-3278; Caplan, A.I., Adult mesenchymal stem cells for tissue engineering versus regenerative medicine (2007) J. Cell. Physiol., 213, pp. 341-347; Horwitz, E.M., MSC: A coming of age in regenerative medicine (2006) Cytotherapy, 8, pp. 194-195; Sumanasinghe, R.D., Bernacki, S.H., Loboa, E.G., Osteogenic differentiation of human mesenchymal stem cells in collagen matrices: Effect of uniaxial cyclic tensile strain on bone morphogenetic protein (BMP-2) mRNA expression (2006) Tissue Eng., 12, pp. 3459-3465; Granero-Molto, F., Weis, J.A., Longobardi, L., Spagnoli, A., Role of mesenchymal stem cells in regenerative medicine: Application to bone and cartilage repair (2008) Expert Opin. Biol. Ther., 8, pp. 255-268; Markusen, J.F., Mason, C., Hull, D.A., Town, M.A., Tabor, A.B., Clements, M., Boshoff, C.H., Dunnill, P., Behavior of adult human mesenchymal stem cells entrapped in alginate-GRGDY beads (2006) Tissue Eng., 12, pp. 821-830; Duggal, S., Fronsdal, K.B., Szoke, K., Shahdadfar, A., Melvik, J.E., Brinchmann, J.E., Phenotype and gene expression of human mesenchymal stem cells in alginate scaffolds (2009) Tissue Eng., Part A, 15, pp. 1763-1773; Kasper, G., Dankert, N., Tuischer, J., Hoeft, M., Gaber, T., Glaeser, J.D., Zander, D., Duda, G.N., Mesenchymal stem cells regulate angiogenesis according to their mechanical environment (2007) Stem Cells, 25, pp. 903-910; Gruber, R., Kandler, B., Holzmann, P., Vogele-Kadletz, M., Losert, U., Fischer, M.B., Watzek, G., Bone marrow stromal cells can provide a local environment that favors migration and formation of tubular structures of endothelial cells (2005) Tissue Eng., 11, pp. 896-903; Valarmathi, M.T., Yost, M.J., Goodwin, R.L., Potts, J.D., A three-dimensional tubular scaffold that modulates the osteogenic and vasculogenic differentiation of rat bone marrow stromal cells (2008) Tissue Eng., Part A, 14, pp. 491-504; Potapova, I.A., Gaudette, G.R., Brink, P.R., Robinson, R.B., Rosen, M.R., Cohen, I.S., Doronin, S.V., Mesenchymal stem cells support migration, extracellular matrix invasion, proliferation, and survival of endothelial cells in vitro (2007) Stem Cells, 25, pp. 1761-1768; Moon, J.J., West, J.L., Vascularization of engineered tissues: Approaches to promote angiogenesis in biomaterials (2008) Curr. Top. Med. Chem., 8, pp. 300-310; Carano, R.A.D., Filvaroff, E.H., Angiogenesis and bone repair (2003) Drug Discovery Today, 8, pp. 980-989; Eriksen, E.F., Eghbali-Fatourechi, G.Z., Khosla, S., Remodeling and vascular spaces in bone (2007) J. Bone Miner. Res., 22, pp. 1-6; Schroeder, T.M., Jensen, E.D., Westendorf, J.J., Runx2: A master organizer of gene transcription in developing and maturing osteoblasts (2005) Birth Defects Res., Part C, 75, pp. 213-225; Soares, R., Guo, S., Ga'rtner, F., Schmitt, F., Russo, J., 17β-Estradiol-mediated vessel assembly and stabilization in tumor angiogenesis requires TGFβ and EGFR crosstalk (2003) Angiogenesis, 6, pp. 271-281; Kubota, Y., Kleinman, H.K., Martin, G.R., Lawley, T.J., Role of laminin and basement membrane in the morphological differentiation of human endothelial cells into capillary-like structures (1988) J. Cell Biol., 107, pp. 1589-1598; Kaully, T., Kaufman-Francis, K., Lesman, A., Levenberg, S., Vascularization-The conduit to viable engineered tissues (2009) Tissue Eng., Part B, 15, pp. 159-169; Silva, E.A., Mooney, D.J., Spatiotemporal control of vascular endothelial growth factor delivery from injectable hydrogels enhances angiogenesis (2007) J. Thromb. Haemost., 5, pp. 590-598; Fuchs, S., Jiang, X., Schmidt, H., Dohle, E., Ghanaati, S., Orth, C., Hofmann, A., Kirkpatrick, C.J., Dynamic processes involved in the pre-vascularization of silk fibroin constructs for bone regeneration using outgrowth endothelial cells (2009) Biomaterials, 30, pp. 1329-1338; Hsiong, S.X., Mooney, D.J., Regeneration of vascularized bone (2006) Periodontol. 2000, 41, pp. 109-122; Abbah, S., Lu, W., Chan, D., Cheung, K., Liu, W., Zhao, F., Li, Z., Luk, K., Osteogenic behavior of alginate encapsulated bone marrow stromal cells: An in vitro study (2008) J. Mater. Sci.: Mater. Med., 19, pp. 2113-2119; Moioli, E.K., Hong, L., Mao, J.J., Inhibition of osteogenic differentiation of human mesenchymal stem cells (2007) Wound Repair Regen., 15, pp. 413-421; Healy, K.E., Guldberg, R.E., Bone tissue engineering (2007) J. Musculoskelet. Neuronal Interact., 7, pp. 328-330; Stein, G.S., Lian, J.B., Owen, T.A., Relationship of cell growth to the regulation of tissue-specific gene expression during osteoblast differentiation (1990) FASEB J., 4, pp. 3111-3123; Lian, J.B., Stein, G.S., Concepts of osteoblast growth and differentiation: Basis for modulation of bone cell development and tissue formation (1992) Crit. Rev. Oral Biol. Med., 3, pp. 269-305; Huang, Y.-C., Kaigler, D., Rice, K.G., Krebsbach, P.H., Mooney, D.J., Combined angiogenic and osteogenic factor delivery enhances bone marrow stromal cell-driven bone regeneration (2005) J. Bone Miner. Res., 20, pp. 848-857; Fang, T.D., Salim, A., Xia, W., Nacamuli, R.P., Guccione, S., Song, H.M., Carano, R.A., Longaker, M.T., Angiogenesis is required for successful bone induction during distraction osteogenesis (2005) J. Bone Miner. Res., 20, pp. 1114-1124; Villars, F., Bordenave, L., Bareille, R., Amédée, J., Effect of human endothelial cells on human bone marrow stromal cell phenotype: Role of VEGF (2000) J. Cell. Biochem., 79, pp. 672-685; Kaigler, D., Krebsbach, P.H., Polverini, P.J., Mooney, D.J., Role of vascular endothelial growth factor in bone marrow stromal cell modulation of endothelial cells (2003) Tissue Eng., 9, pp. 95-103; Grellier, M., Ferreira-Tojais, N., Bourget, C., Bareillke, R., Guillemot, F., Amédée, J., Role of vascular endothelial growth factor in the communication between human osteoprogenitors and endothelial cells (2009) J. Cell. Biochem., 106, pp. 390-398; Yu, J., Gu, Y., Du, K.T., Mihardja, S., Sievers, R.E., Lee, R.J., The effect of injected RGD modified alginate on angiogenesis and left ventricular function in a chronic rat infarct model (2009) Biomaterials, 30, pp. 751-756
Keywords: Alginate; Alginates; alginic acid; alkaline phosphatase; Alkaline phosphatase activity; angiogenesis; arginylglycylaspartic acid; article; Basal conditions; Base Sequence; Binary composition; bone development; Bone tissue engineering; Cell culture; cell differentiation; Cell extension; Cell immobilization; cell metabolism; cell structure; cell viability; collagen type 1; Collagen type I; controlled study; DNA Primers; Endothelial Cells; endothelium cell; enzyme activity; human; human cell; Human mesenchymal stem cells; Humans; immobilized cell; Immobilized cells; Low molecular weight; matrix; Mesenchymal stem cell; Mesenchymal Stem Cells; Metabolic activity; Microscopy, Electron, Scanning; microsphere; Microspheres; molecular weight; Neovascularization, Physiologic; nucleotide sequence; Oligopeptides; osteoblast; Osteogenic; Phosphatases; priority journal; protein expression; quantitative analysis; Reverse Transcriptase Polymerase Chain Reaction; stem cell; Stem cells; three dimensional imaging; Tissue engineering; transcription factor RUNX2; umbilical vein; Up-regulation; upregulation

Influence of crystallite size of nanophased hydroxyapatite on fibronectin and osteonectin adsorption and on MC3T3-E1 osteoblast adhesion and morphology - Ribeiro, N.; Sousa, S.R.; Monteiro, F.J. (Journal of Colloid and Interface ScienceJ. Colloid Interface Sci., 2010)
The characteristic topographical features (crystallite dimensions, surface morphology and roughness) of bioceramics may influence the adsorption of proteins relevant to bone regeneration. This work aims at analyzing the influence of two distinct nanophased hydroxyapatite (HA) ceramics, HA725 and HA1000 on fibronectin (FN) and osteonectin (ON) adsorption and MC3T3-E1 osteoblast adhesion and morphology. Both substrates were obtained using the same hydroxyapatite nanocrystals aggregates and applying the sintering temperatures of 725°C and 1000°C, respectively. The two proteins used in this work, FN as an adhesive glycoprotein and ON as a counter-adhesive protein, are known to be involved in the early stages of osteogenesis (cell adhesion, mobility and proliferation). The properties of the nanoHA substrates had an important role in the adsorption behavior of the two studied proteins and clearly affected the MC3T3-E1 morphology, distribution and metabolic activity. HA1000 surfaces presenting slightly larger grain size, higher root-mean-square roughness (Rq), lower surface area and porosity, allowed for higher amounts of both proteins adsorbed. These substrates also revealed increased number of exposed FN cell-binding domains as well as higher affinity for osteonectin. Regarding the osteoblast adhesion results, improved viability and cell number were found for HA1000 surfaces as compared to HA725 ones, independently of the presence or type of adsorbed protein. Therefore the osteoblast adhesion and metabolic activity seemed to be more sensitive to surfaces morphology and roughness than to the type of adsorbed proteins. © 2010 Elsevier Inc.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: JCISAdoi: 10.1016/j.jcis.2010.08.013PubMed ID: 20810127Language of Original Document: EnglishCorrespondence Address: Ribeiro, N.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: nribeiro@ineb.up.ptChemicals/CAS: fibronectin, 86088-83-7; hydroxyapatite, 1306-06-5, 51198-94-8; osteonectin, 104052-78-0; protein, 67254-75-5; Ceramics; Durapatite, 1306-06-5; Fibronectins; OsteonectinReferences: Griffith, L.G., Naughton, G., (2002) Science, 295, p. 1009;Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., (2000) J. Biomed. Mater. Res., 51, pp. 475-483; Webster, T.J., Siegel, R.W., Bizios, R., (1999) Biomaterials, 20, pp. 1221-1227; Jun, I.K., Jang, J.H., Kim, H.W., Kim, H.E., (2005) J. Mater. Sci., 40, pp. 2891-2895; Geiger, B., Bershadsky, A., Pankov, R., Yamada, K.M., (2001) Nat. Rev. Mol. Cell Biol., 2, pp. 793-805; Globus, R.K., Doty, S.B., Lull, J.C., Holmuhamedov, E., Humphries, M.J., Damsky, C.H., (1998) J. Cell Sci., 111, pp. 1385-1393; Moursi, A.M., Damsky, C.H., Lull, J., Zimmerman, D., Doty, S.B., Aota, S.I., Globus, R.K., (1996) J. Cell Sci., 109, pp. 1369-1380; Garcia, A.J., Vega, M.D., Boettiger, D., (1999) Mol. Biol. Cell, 10, pp. 785-798; Petrie, T.A., Capadona, J.R., Reyes, C.D., Garcia, A.J., (2006) Biomaterials, 27, pp. 5459-5470; Dolatshahi-Pirouz, A., Jensen, T., Foss, M., Chevallier, J., Besenbacher, F., (2009) Langmuir, 25, pp. 2971-2978; Shen, J.-W., Wu, T., Wang, Q., Pan, H.-H., (2008) Biomaterials, 29, pp. 513-532; Brekken, R.A., Sage, E.H., (2000) Matrix Biol., 19, pp. 569-580; Termine, J.D., Kleinman, H.K., Whitson, S.W., Conn, K.M., McGarvey, M.L., Martin, G.R., (1981) Cell, 26, pp. 99-105; Liao, S., Ngiam, M., Chan, C.K., Ramakrishna, S., (2009) Biomed. Mater., 4; Sarvestani, A.S., He, X., Jabbari, E., (2008) Eur. Biophys. J. Biophys. Lett., 37, pp. 229-234; Majeska, R.J., Cell Biology of Bone (1934), pp. 2-3. , in: S.C. Cowin (Ed.), Bone Mechanics HandbookKoblinski, J.E., Wu, M., Demeler, B., Jacob, K., Kleinman, H.K., (2005) J. Cell Sci., 118, pp. 2965-2974; O'Brien, J., Wilson, I., Orton, T., Pognan, F., (2000) Eur. J. Biochem., 267, pp. 5421-5426; Ribeiro, C.C., Gibson, I., Barbosa, M.A., (2006) Biomaterials, 27, pp. 1749-1761; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., (1999) J. Biomed. Mater. Res., 45, pp. 370-375; Suzuki, T., Nishizawa, K., Yokogawa, Y., Nagata, F., Kawamoto, Y., Kameyama, T., (1996) J. Ferment. Bioeng., 81, pp. 226-232; Suzuki, T., Yamamoto, T., Toriyama, M., Nishizawa, K., Yokogawa, Y., Mucalo, M.R., Kawamoto, Y., Kameyama, T., (1997) J. Biomed. Mater. Res., 34, pp. 507-517; Holland, N.B., Marchant, R.E., (2000) J. Biomed. Mater. Res., 51, pp. 307-315; Kothapalli, C., Wei, M., Vasiliev, A., Shaw, M.T., (2004) Acta Mater., 52, pp. 5655-5663; Sousa, S.R., Manuela Bras, M., Moradas-Ferreira, P., Barbosa, M.A., (2007) Langmuir, 23, pp. 7046-7054; Rouahi, M., Champion, E., Gallet, O., Jada, A., Anselme, K., (2006) Colloids Surf., B - Biointerfaces, 47, pp. 10-19; dos Santos, E.A., Farina, M., Soares, G.A., Anselme, K., (2008) J. Mater. Sci. - Mater. Med., 19, pp. 2307-2316; Amaral, I.F., Unger, R.E., Fuchs, S., Mendonca, A.M., Sousa, S.R., Barbosa, M.A., Pego, A.P., Kirkpatrick, C.J., (2009) Biomaterials, 30, pp. 5465-5475; Sousa, S.R., Moradas-Ferreira, P., Barbosa, M.A., (2005), pp. 1173-1178. , TiO2 type influences fibronectin adsorption, in: 19th Conference of the European-Society-for-Biomaterials, Springer, Sorrento, ItalyGoldstein, A.S., DiMilla, P.A., (2002) J. Biomed. Mater. Res., 59, pp. 665-675; Michael, K.E., Vernekar, V.N., Keselowsky, B.G., Meredith, J.C., Latour, R.A., Garcia, A.J., (2003) Langmuir, 19, pp. 8033-8040; Anselme, K., Bigerelle, M., (2005) Acta Biomater., 1, pp. 211-222; Anselme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Iost, A., Hardouin, P., (2000) J. Biomed. Mater. Res., 49, pp. 155-166; Wang, C., Duan, Y., Markovic, B., Barbara, J., Rolfe Howlett, C., Zhang, X., Zreiqat, H., (2004) Biomaterials, 25, pp. 2949-2956; Smith, I.O., McCabe, L.R., Baumann, M.J., (2006) Int. J. Nanomed., 1, pp. 189-194; Bernards, M.T., Qin, C.L., Jiang, S.Y., Bone osteopontin, and bovine serum albumin (2008) Colloids Surf., B - Biointerfaces, 64, pp. 236-247; Durrieu, M.C., Pallu, S., Guillemot, F., Bareille, R., Amedee, J., Baquey, C., Labrugere, C., Dard, M., (2004) J. Mater. Sci. - Mater. Med., 15, pp. 779-786; Itoh, D., Yoneda, S., Kuroda, S., Kondo, H., Umezawa, A., Ohya, K., Ohyama, T., Kasugai, S., (2002) J. Biomed. Mater. Res., 62, pp. 292-298; Funk, S.E., Sage, E.H., (1993) J. Cell. Physiol., 154, pp. 53-63; Hagan, S., Hiscott, P., Sheridan, C., Wong, D., Grierson, I., McGalliard, J., (2003) Mol. Vis., 9, pp. 87-92; Deligianni, D., Korovessis, P., Porte-Derrieu, M.C., Amedee, J., (2005) J. Spinal Disord. Technol., 18, pp. 257-262; Nelson, M., Balasundaram, G., Webster, T.J., (2006) Int. J. Nanomed., 1, pp. 339-349
Keywords: Adhesion; Adhesive proteins; Adsorption; Adsorption behavior; Animals; Apatite; article; Bioceramics; Biological materials; Biomaterials; bone development; Bone Regeneration; cell adhesion; Cell Count; cell metabolism; cell motility; Cell number; cell proliferation; cell strain 3T3; cell structure; Cell-binding domain; Cells, Cultured; cellular distribution; ceramics; controlled study; Crystallite dimension; Crystallite size; Crystallization; Durapatite; Fibronectin; Fibronectin adsorption; Fibronectins; glycoprotein; grain; Grain size; human; human cell; hydroxyapatite; Hydroxyapatite nanocrystals; MC3T3-E1; Metabolic activity; metabolism; Mice; morphology; Nano-HA; nanocrystal; nanoparticles; Nanophased hydroxyapatite; osteoblast; Osteoblast adhesion; Osteoblast morphology; Osteoblasts; Osteogenesis; osteonectin; Osteonectin adsorption; Particle Size; porosity; priority journal; protein; Proteins; Root mean square roughness; Sintering; Sintering temperatures; Surface area; Surface Properties; surface property; Surface roughness; temperature; Topographical features

The MEE principle in data classification: A perceptron-based analysis - Silva, L.M.; Marques de Sá, J.; Alexandre, L.A. (Neural ComputationNeural Comp., 2010)
This letter focuses on the issue of whether risk functionals derived from information-theoretic principles, such as Shannon or Rényi's entropies, are able to cope with the data classification problem in both the sense of attaining the risk functional minimum and implying the minimum probability of error allowed by the family of functions implemented by the classifier, here denoted by min Pe. The analysis of this so-called minimization of error entropy (MEE) principle is carried out in a single perceptron with continuous activation functions, yielding continuous error distributions. In spite of the fact that the analysis is restricted to single perceptrons, it reveals a large spectrum of behaviors that MEE can be expected to exhibit in both theory and practice. In what concerns the theoretical MEE, our study clarifies the role of the parameters controlling the perceptron activation function (of the squashing type) in often reaching the minimum probability of error. Our study also clarifies the role of the kernel density estimator of the error density in achieving the minimum probability of error in practice. © 2010 Massachusetts Institute of Technology.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1162/NECO_a_00013PubMed ID: 20569178Language of Original Document: EnglishCorrespondence Address: Silva, L.M.; Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Porto 4200-465, Portugal; email: lmsilva@fe.up.ptReferences: Alexandre, L.A., Marques de Sá, J., Error entropy minimization for LSTM training (2006) Proceedings of the 16th International Conference on Artificial Neural Networks, pp. 244-253. , Berlin: Springer;Asuncion, A., Newman, D., (2007) UCI machine learning repository. Irvine University of California, Irvine, , http://www.ics.uci.edu/~mlearn/MLRepository.html, School of Information and Computer Sciences. Available online at; Bishop, C., (1995) Neural networks for pattern recognition, , New York: OxfordUniversity Press; Erdogmus, D., Hild K., II., Príncipe, J.C., Blind source separation using Rényi's α-marginal entropies (2002) Neurocomputing, 49, pp. 25-38; Erdogmus, D., Príncipe, J.C., Comparison of entropy and mean square error criteria in adaptive system training using higher order statistics (2000) Proceedings of the Intl. Conf. on ICA and Signal Separation, pp. 75-80. , Berlin: Springer-Verlag; Erdogmus, D., Príncipe, J.C., An error-entropy minimization algorithm for supervised training of nonlinear adaptive systems (2002) IEEE Transactions on Signal Processing, 50 (7), pp. 1780-1786; Erdogmus, D., Príncipe, J.C., Convergence properties and data efficiency of the minimum error entropy criterion in adaline training (2003) IEEE Transactions on Signal Processing, 51 (7), pp. 1966-1978; Gokcay, E., Príncipe, J.C., Information theoretic clustering (2002) IEEE Trans. on Pattern Analysis and Machine Learning, 24 (2), pp. 158-171; Han, L., Kernel partial least squares (K-PLS) for scientific data mining. Unpublished doctoral dissertation (2007) Rensselaer Polytechnic Institute; Hild, I.I., Erdogmus, K., Príncipe D., J.C., Blind source separation using Rényi's mutual information (2001) IEEE Signal Processing Letters, 8, pp. 174-176; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, 3, pp. 79-87; Jenssen, R., Hild, K., Erdogmus, D., Príncipe, J.-C., Eltoft, T., Clustering using Rényis entropy (2003) Proceedings of the Int. Joint Conference on Neural Networks, pp. 523-528. , Piscataway, NJ: IEEE Press; Johnson, N., Kotz, S., (1970) Continuous univariate distributions, , Hoboken, NJ:Wiley; Kapur, J., Maximum-entropy models in science and engineering (1993), (rev. ed.). Hoboken, NJ: WileyLagarias, J., Reeds, J.A., Wright, M.H., Wright, P.E., Convergence properties of the nelder-mead simplex method in low dimensions (1998) SIAM Journal of Optimization, 9 (1), pp. 112-147; Linsker, R., Self-organization in a perceptual network (1988) IEEE Computer, 21, pp. 105-117; Liu, W., Pokharel, P., Príncipe, J., Correntropy: Properties and applications in non-gaussian signal processing (2007) IEEE Transactions on Signal Processing, 55 (11), pp. 5286-5298; Parzen, E., On the estimation of a probability density function and the mode (1962) Annals of Mathematical Statistics, 33, pp. 1065-1076; Príncipe, J.C., Xu, D., Fisher, J., Information theoretic learning (2000) Unsupervised adaptive filtering, 1, pp. 265-319. , S. Haykin (Ed.), Blind source separation, Hoboken, NJ: Wiley; Rényi, A., (1970) Probability theory, , Dordrecht: North-Holland; Richard, M., Lippmann, R., Neural network classifiers estimate Bayesian a posteriori probabilities (1991) Neural Computation, 3, pp. 461-483; Santos, J., (2007) Data classification with neural networks and entropic criteria, , Unpublished doctoral dissertation, University of Porto; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Batch-sequential algorithm for neural networks trained with entropic criteria (2005) Proceedings of the International Conference on Artificial Neural Networks, pp. 91-96. , Berlin: Springer-Verlag; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Legclust-a clustering algorithm based on layered entropic subgraphs (2007) IEEE Transactions on Pattern Analysis and Machine Intelligence, 30 (1), pp. 62-75; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Sereno, F., Optimization of the error entropy minimization algorithm for neural network classification (2004) Intelligent engineering systems through artificial neural networks, pp. 81-86. , C. Dagli, A. Buczak, D. Enke, M. Embrechts, & O. Ersoy (Eds.), Washington, DC: ASME; Silva, L.M., (2008) Neural networks with error-density risk functionals for data classification, , Unpublished doctoral dissertation, University of Porto; Silva, L.M., Embrechts, M., Santos, J.M., Marques de Sá, J., The influence of the risk functional in data classification with MLPs (2008) Proceedings of the International Conference on Artificial Neural Networks, pp. 185-194. , Berlin: Springer-Verlag; Silva, L.M., Felgueiras, C., Alexandre, L.A., Marques de Sá, J., Error entropy in classification problems: A univariate data analysis (2006) Neural Computation, 18 (9), pp. 2036-2061; Silva, L.M., Marques de Sá, J., Alexandre, L.A., Neural network classification using Shannon's entropy (2005) Proceedings of the European Symposium on Artificial Neural Networks, pp. 217-222. , Bruges: d-side; Stoller, D., Univariate two-population distribution free discrimination (1954) Journal of the American Statistical Association, 49, pp. 770-777; Thompson, J., Tapia, R., (1978) Nonparametric probability density estimation, , Baltimore, MD: Johns Hopkins University Press; Watanabe, S., Pattern recognition as a quest for minimum entropy (1981) Pattern Recognition, 13 (5), pp. 381-387
Keywords: algorithm; Algorithms; artificial intelligence; artificial neural network; automated pattern recognition; Computer simulation; entropy; letter; Mathematical Concepts; mathematical phenomena; Models, Statistical; Neural Networks (Computer); Pattern Recognition, Automated; standard; statistical model

A model for educational simulation of hemodynamic transitions at birth - Sá-Couto, C.D.; Andriessen, P.; van Meurs, W.L.; Ayres-de-Campos, D.; Sá-Couto, P.M. (Pediatric ResearchPediatr. Res., 2010)
Birth is characterized by swift and complex transitions in hemodynamic and respiratory variables. Unrecognized pathologies or incidents may quickly become fatal or cause permanent damage. This article introduces an essential component of an acute perinatal care simulator, namely a model for educational simulation of normal hemodynamic transitions seen during and shortly after birth. We explicitly formulate educational objectives and adapt a preexisting model for the simulation of neonatal cardiovascular physiology to include essential aspects of fetal hemodynamics. From the scientific literature, we obtain model parameters that characterize these aspects quantitatively. The fetal model is controlled by a time-and event-based script of changes occurring at birth, such as onset of breathing and cord clamping, and the transitory phase up to 24 h after birth. Comparison of simulation results with published target data confirms that realistic simulated hemodynamic vital signs are achieved. Copyright © 2010 International Pediatric Research Foundation, Inc.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: PEREBdoi: 10.1203/PDR.0b013e3181c2def3Language of Original Document: EnglishCorrespondence Address: Van Meurs, W. L.; INEB-Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUP, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: wvanmeurs@ineb.up.ptReferences: Van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit, 13, pp. 317-324;Sá Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Andriessen, P., A model for educational simulation of neonatal cardiovascular pathophysiology (2006) Simul Healthc, 1, pp. 4-9; Zijlmans, M., Sá-Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Andriessen, P., Corrected and improved model for educational simulation of neonatal cardiovascular pathophysiology (2009) Simul Healthc, 4, pp. 49-53; Goodwin, J.A., Van Meurs, W.L., Sá Couto, C.D., Beneken, J.E., Graves, S.A., A model for educational simulation of infant cardiovascular physiology (2004) Anesth Analg, 99, pp. 1655-1664; Ménigault, E., Vieyres, P., Lepoivre, B., Durand, A., Pourcelot, L., Berson, M., Fetal heart modelling based on a pressure-volume relationship (1997) Med Biol Eng Comput, 35, pp. 715-721; Pennati, G., Bellotti, M., Fumero, R., Mathematical modeling of the human foetal cardiovascular system based on Doppler ultrasound data (1997) Med Eng Phys, 19, pp. 327-335; Huikeshoven, F., Coleman, T.G., Jongsma, H.W., Mathematical model of the fetal cardiovascular system: The uncontrolled case (1980) Am J Physiol, 239, pp. R317-R325; Mielke, G., Benda, N., Cardiac output and central distribution of blood flow in the human fetus (2001) Circulation, 103, pp. 1662-1668; Cunningham, G., Leveno, K., MacDonald, P., Gilstrap III, L., Gant, N., Hankins, G., Clark, S., The morphological and functional development of the fetus (1996) Williams Obstetrics, pp. 151-190. , Cunningham G, Leveno K, MacDonald P, Gilstrap III L, Gant N, Hankins G, Clark S (eds) 20th Ed. Appleton & Lange, CT; Huikeshoven, F.J., Hope, I.D., Power, G.G., Gilbert, R.D., Longo, L.D., Mathematical model of fetal circulation and oxygen delivery (1985) Am J Physiol, 249, pp. R192-R202; Rasanen, J., Wood, D.C., Weiner, S., Ludomirski, A., Huhta, J.C., Role of the pulmonary circulation in the distribution of human fetal cardiac output during the second half of pregnancy (1996) Circulation, 94, pp. 1068-1073; Assali, N.S., Morris, J.A., Beck, R., Cardiovascular hemodynamics in the fetal lamb before and after lung expansion (1965) Am J Physiol, 208, pp. 122-129; Vilos, G.A., Liggins, G.C., Intrathoracic pressures in fetal sheep (1982) J Dev Physiol, 4, pp. 247-256; Hooper, S.B., Wallace, M.J., Role of the physicochemical environment in lung development (2006) Clin Exp Pharmacol Physiol, 33, pp. 273-279; Greenspan, J.S., Shaffer, T.H., Fox, W.W., Spitzer, A.R., Assisted ventilation: Physiologic implications and complications (1998) Fetal and Neonatal Physiology, 2. , Polin RA, Fox WW (eds) W.B. Saunders Company, Philadelphia, PA; Friedman, A.H., Fahey, J.T., The transitions from fetal to neonatal circulation: Normal responses and implications for infants with heart disease (1993) Semin Perinatol, 17, pp. 106-121; Ghanayem, N.S., Gordon, J.B., Modulation of pulmonary vasomotor tone in the fetus and neonate (2001) Respir Res, 2, pp. 139-144; Dawes, G.S., Mott, J.C., Widdicombe, J.G., Wyatt, D.G., Changes in the lungs of the new-born lamb (1953) J Physiol, 121, pp. 141-162; Brook, M.M., Heymann, M.A., Teitel, D.F., The heart (2001) Care of the High-Risk, , Klaus MH, Fanaroff AA (eds) 5th ed. W.B. Saunders Company, Philadelphia, PA; Gutyon, A.C., Fetal and neonatal physiology (1991) Textbook of Medical Physiology, , Guyton AC (ed) 8th ed. W.B. Saunders Company Philadelphia, PA; Lagercrantz, H., Bistoletti, P., Catecholamine release in the newborn infant at birth (1977) Pediatr Res, 11, pp. 889-893; Padbury, J.F., Diakomanolis, E.S., Hobel, C.J., Perelman, A., Fisher, D.A., Neonatal adaptation: Sympatho-adrenal response to umbilical cord cutting (1981) Pediatr Res, 15, pp. 1483-1487; Minoura, S., Gilbert, R.D., Postnatal change of cardiac function in lambs: Effects of ganglionic block and afterload (1987) J Dev Physiol, 9, pp. 123-135; Coskun, S., Yüksel, H., Bilgi, Y., Lacin, S., Tansug, N., Onag, A., Non-invasive evaluation of the adaptations of cardiac function in the neonatal period: A comparison of healthy infants delivered by vaginal route and caesarean section (2001) Acta Med Okayama, 55, pp. 213-218; Kishkurno, S., Takahashi, Y., Harada, K., Ishida, A., Tamura, M., Takada, G., Postnatal changes in left ventricular volume and contractility in healthy term infants (1997) Pediatric Cardiology, 18 (2), pp. 91-95. , DOI 10.1007/s002469900123; Shiota, T., Harada, K., Takada, G., Left ventricular systolic and diastolic function during early neonatal period using transthoracic echocardiography (2002) Tohoku J Exp Med, 197, pp. 151-158; Walther, F.J., Benders, M.J., Leighton, J.O., Early changes in the neonatal circulatory transition (1993) J Pediatr, 123, pp. 625-632; Hiraishi, S., Misawa, H., Oguchi, K., Kadoi, N., Saito, K., Fujino, N., Hojo, M., Yashiro, K., Two-dimensional Doppler echocardiographic assessment of closure of the ductus arteriosus in normal newborn infants (1987) J Pediatr, 111, pp. 755-760; Migliavacca, F., Dubini, G., Pennati, G., Pietrabissa, R., Fumero, R., Hsia, T.Y., De Leval, M.R., Computational model of the fluid dynamics in systemic-to-pulmonary shunts (2000) J Biomech, 33, pp. 549-557; Teitel, D.F., Iwamoto, H.S., Rudolph, A.M., Effects of birth-related events on central blood flow patterns (1987) Pediatr Res, 22, pp. 557-566; Anderson, D.F., Bissonnette, J.M., Faber, J.J., Thornburg, K.L., Central shunt flows and pressures in the mature fetal lamb (1981) Am J Physiol, 241, pp. H60-H66; Agata, Y., Hiraishi, S., Oguchi, K., Misawa, H., Horiguchi, Y., Fujino, N., Yashiro, K., Shimada, N., Changes in left ventricular output from fetal to early neonatal life (1991) J Pediatr, 119, pp. 441-445; Harada, K., Shiota, T., Takahashi, Y., Tamura, M., Takada, G., Changes in the volume and performance of the left ventricle in the early neonatal period (1994) Early Hum Dev, 39, pp. 201-209; Moss, A.J., Emmanouilides, G.C., Adams, F.H., Chuang, K., Response of ductus arteriosus and pulmonary and systemic arterial pressure to changes in oxygen environment in newborn infants (1964) Pediatrics, 33, pp. 937-944; Emmanouilides, G.C., Moss, A.J., Monset-Couchard, M., Marcano, B.A., Rzeznic, B., Cardiac output in newborn infants (1970) Biol Neonate, 15, pp. 186-197; Emmanouilides, G.C., Moss, A.J., Duffie Jr., E.R., Adams, F.H., Pulmonary arterial pressure changes in human newborn infants from birth to 3 days of age (1964) J Pediatr, 65, pp. 327-333; Soni, N., Williams, P., Positive pressure ventilation: What is the real cost? (2008) Br J Anaesth, 101, pp. 446-457; Moss, A.J., Emmanouilides, G.C., Duffie Jr., E.R., Closure of the ductus arteriosus in the newborn infant (1963) Pediatrics, 32, pp. 25-30
Keywords: article; artificial ventilation; biological model; birth; Blood flow; blood flow velocity; blood pressure; breathing; breathing mechanics; cardiovascular function; clamp; comparative study; Computer simulation; Constriction; education; evaluation; fetus; hemodynamics; human; Humans; Infant, Newborn; ligation; Models, Cardiovascular; newborn; Parturition; perinatal care; priority journal; Regional Blood Flow; reproducibility; Reproducibility of Results; Respiration, Artificial; Respiratory Mechanics; scientific literature; simulator; stimulation; time; Time Factors; umbilical cord; vascularization; vital sign

Monitoring incremental histogram distribution for change detection in data streams - Sebastião, R.; Gama, J.; Rodrigues, P.P.; Bernardes, J. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2010)
Histograms are a common technique for density estimation and they have been widely used as a tool in exploratory data analysis. Learning histograms from static and stationary data is a well known topic. Nevertheless, very few works discuss this problem when we have a continuous flow of data generated from dynamic environments. The scope of this paper is to detect changes from high-speed time-changing data streams. To address this problem, we construct histograms able to process examples once at the rate they arrive. The main goal of this work is continuously maintain a histogram consistent with the current status of the nature. We study strategies to detect changes in the distribution generating examples, and adapt the histogram to the most recent data by forgetting outdated data. We use the Partition Incremental Discretization algorithm that was designed to learn histograms from high-speed data streams. We present a method to detect whenever a change in the distribution generating examples occurs. The base idea consists of monitoring distributions from two different time windows: the reference window, reflecting the distribution observed in the past; and the current window which receives the most recent data. The current window is cumulative and can have a fixed or an adaptive step depending on the distance between distributions. We compared both distributions using Kullback-Leibler divergence, defining a threshold for change detection decision based on the asymmetry of this measure. We evaluated our algorithm with controlled artificial data sets and compare the proposed approach with nonparametric tests. We also present results with real word data sets from industrial and medical domains. Those results suggest that an adaptive window's step exhibit high probability in change detection and faster detection rates, with few false positives alarms. © 2010 Springer-Verlag Berlin Heidelberg.
Conference code: 81882Cited By (since 1996): 1Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-12519-5_2Language of Original Document: EnglishCorrespondence Address: Sebastião, R.; LIAAD, INESC Porto, L.A. Rua de Ceuta, 118, 6, Porto 4050-190, Portugal; email: raquel@liaad.up.ptReferences: Ayres-De-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto® 3.5 - A central fetal monitoring station with online alerts based on computerized cardiotocogram+ST event analysis (2008) J. Perinat. Med., 36, pp. 260-264;Ayres-De-Campos, D., Bernardes, J., Garrido, A., Marques-De-Śa, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J. Matern Fetal Med., 9, pp. 311-318; Barbaŕa, D., Requirements for clustering data streams (2002) SIGKDD Explorations (Special Issue on Online, Interactive and Anytime Data Mining), 3 (2), pp. 23-27; Berthold, M., Hand, D., (1999) Intelligent Data Analysis-An Introduction., , Springer, Heidelberg; Breiman, L., (1993) Classification and Regression Trees., , Chapman & Hall, Boca Raton; Bock, R.K., Savicky, P., (2007) MAGIC Gamma Telescope Benchmark, , http://archive.ics.uci.edu/ml/datasets.html; Chabert, M., Ruiz, D., Tourneret, J.-Y., Optimal wavelet for abrupt change detection in multiplicative noise (2004) IEEE International Conference on Acoustics Speech and Signal Processing, pp. 1089-1092. , May 2004; Cormode, G., Garofalakis, M., Sketching probabilistic data streams (2007) Proceedings of the 2007 ACM SIGMOD International Conference on Management of Data, pp. 281-292. , June 2007; Correa, M., De, J., Raḿirez, M., Bielza, C., Pamies, J., Alique, J.R., Prediction of surface quality using probabilistic models (2007) 7th Congress of the Colombian Association of Automatic, Cali, Colombia, , March 21-24 Spanish; Dasu, T., Krishnan, S., Venkatasubramanian, S., Yi, K., An information-theoretic approach to detecting changes in multi-dimensional data streams (2006) Interface 2006, , Pasadena, CA Report; Gama, J., Medas, P., Castillo, G., Rodrigues, P.P., Learning with drift detection (2004) LNCS (LNAI), 3171, pp. 286-295. , Bazzan, A.L.C., Labidi, S. (eds.) Springer, Heidelberg SBIA 2004; Gama, J., Pinto, C., Discretization from data streams: Applications to histograms and data mining (2006) Proceedings of the 2006 ACM Symposium on Applied Computing, pp. 662-667; Goņcalves, H., Bernardes, J., Paula Rocha, J.A., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Human Development, 83 (9), pp. 585-591; Guha, S., Koudas, N., Woo, J., (2004) REHIST: Relative Error Histogram Construction Algorithms, pp. 300-311. , Proceedings of the VLDB Conference; Guha, S., Harb, B., Wavelet synopsis for data streams: Minimizing non-euclidean error (2005) Proceedings of the Eleventh ACM SIGKDD International Conference on Knowledge Discovery in Data Mining, pp. 88-97. , August 2005; Guha, S., Koudas, N., Shim, K., Approximation and streaming algorithms for histogram construction problems (2006) ACM Transactions on Database Systems (TODS), 31 (1), pp. 396-438; Hulten, G., Spencer, L., Domingos, P., Mining time-changing data streams (2001) Proceedings of the Seventh ACM SIGKDD International Conference on Knowledge Discovery and Data Mining ACM SIGKDD 2001, pp. 97-106. , ACM Press, New York; Jagadish, H.V., Koudas, N., Muthukrishnan, S., Poosala, V., Sevcik, K.C., Suel, T., Optimal histograms with quality guarantees (1998) Proc. of the VLDB Conference, pp. 275-286; Karras, P., Sacharidis, D., Mamoulis, N., Exploiting Duality in Summarization with Deterministic Guarantees. Approximating a Data Stream for Querying and Estimation: Algorithms and Performance Evaluation (2007) Proceedings of the ACM SIGKDD International Conference on Knowledge Discovery and Data Mining (KDD), pp. 380-389; Kifer, D., Ben-David, S., Gehrke, J., (2004) Detecting Change in Data Streams, pp. 180-191. , VLDB 2004: Proceedings of the 30th International Conference on Very Large Data Bases Morgan Kaufmann Publishers Inc., San Francisco; Klinkenberg, R., Renz, I., Adaptive information filtering: Learning in the presence of concept drifts (1998) Learning for Text Categorization, pp. 33-40. , AAAI Press, Menlo Park; Klinkenberg, R., Joachims, T., Detecting concept drift with support vector ma-chines (2000) Proceedings of ICML 2000, 17th International Conference on Machine Learning, Stanford, US, pp. 487-494. , Morgan Kaufmann Publishers, San Francisco; Klinkenberg, R., Learning drifting concepts: Example selection vs. example weight-ing (2004) Intelligent Data Analysis, 8 (3), pp. 281-300; Maloof, M., Michalski, R., Selecting examples for partial memory learning (2000) Machine Learning, 41, pp. 27-52; Pestana, D.D., Velosa, S.F., Introdu̧c̃aòa Probabilidadeèa Estat̀istica (2002) Funda̧c̃ao Calouste Gulbenkian; Pinto, C., Gama, J., Incremental discretization, application to data with concept drift (2007) Proceedings of the 2007 ACM Symposium on Applied Computing, pp. 467-468. , March 2007; Sebastĩao, R., Gama, J., Change detection in learning histograms from data streams (2007) Proceedings of Portuguese Conference on Artificial Intelligence, Guimar̃aes, Portugal, , December; Spinosa, E.J., Carvalho, A., Gama, J., OLINDDA: A cluster-based approach for detecting novelty and concept drift in data streams (2007) Proceedings of the 2007 ACM Symposium on Applied Computing, March 2007, pp. 448-452; Widmer, G., Kubat, M., Learning in the presence of concept drift and hidden contexts (1996) Machine Learning, 23, pp. 69-101
Keywords: Adaptive Cumulative Windows; Change detection; Data communication systems; Data reduction; Data stream; Data streams; Graphic methods; Learning histograms; Learning systems; Machine learning; Machine-learning; Monitoring; Monitoring data distribution; Sensors; signal detection; Statistical methods

Neuropeptide y and osteoblast differentiation - The balance between the neuro-osteogenic network and local control: Review Article - Franquinho, F.; Liz, M.A.; Nunes, A.F.; Neto, E.; Lamghari, M.; Sousa, M.M. (FEBS JournalFEBS J., 2010)
Accumulating evidence has contributed to a novel view in bone biology: bone remodeling, specifically osteoblast differentiation, is under the tight control of the central and peripheral nervous systems. Among other players in this neuro-osteogenic network, the neuropeptide Y (NPY) system has attracted particular attention. At the central nervous system level, NPY exerts its function in bone homeostasis through the hypothalamic Y2 receptor. Locally in the bone, NPY action is mediated by its Y1 receptor. Besides the presence of Y1, a complex network exists locally: not only there is input of the peripheral nervous system, as the bone is directly innervated by NPY-containing fibers, but there is also input from non-neuronal cells, including bone cells capable of NPY expression. The interaction of these distinct players to achieve a multilevel control system of bone homeostasis is still under debate. In this review, we will integrate the current knowledge on the impact of the NPY system in bone biology, and discuss the mechanisms through which the balance between central and the peripheral NPY action might be achieved. © 2010 FEBS.
Cited By (since 1996): 5Export Date: 21 November 2012Source: Scopusdoi: 10.1111/j.1742-4658.2010.07774.xPubMed ID: 20681986Language of Original Document: EnglishCorrespondence Address: Sousa, M. M.; IBMC, Rua Campo Alegre 823, 4150-180 Porto, Portugal; email: msousa@ibmc.up.ptChemicals/CAS: neuropeptide Y, 82785-45-3, 83589-17-7; Leptin; Neuropeptide Y; Protein Isoforms; Receptors, Neuropeptide YReferences: Bellido, T., Ali, A.A., Gubrij, I., Plotkin, L.I., Fu, Q., O'Brien, C.A., Manolagas, S.C., Jilka, R.L., Chronic elevation of parathyroid hormone in mice reduces expression of sclerostin by osteocytes: A novel mechanism for hormonal control of osteoblastogenesis (2005) Endocrinology, 146, pp. 4577-4583;Keller, H., Kneissel, M., SOST is a target gene for PTH in bone (2005) Bone, 37, pp. 148-158; O'Brien, C.A., Plotkin, L.I., Galli, C., Goellner, J.J., Gortazar, A.R., Allen, M.R., Robling, A.G., Turner, C.H., Control of bone mass and remodeling by PTH receptor signaling in osteocytes (2008) PLoS ONE, 3, p. 2942; Robling, A.G., Niziolek, P.J., Baldridge, L.A., Condon, K.W., Allen, M.R., Alam, I., Mantila, S.M., Harris, S.E., Mechanical stimulation of bone in vivo reduces osteocyte expression of Sost/sclerostin (2008) J Biol Chem, 283, pp. 5866-5875; Tatsumi, S., Ishii, K., Amizuka, N., Li, M., Kobayashi, T., Kohno, K., Ito, M., Ikeda, K., Targeted ablation of osteocytes induces osteoporosis with defective mechanotransduction (2007) Cell Metab, 5, pp. 464-475; McDonald, A.C., Schuijers, J.A., Shen, P.J., Gundlach, A.L., Grills, B.L., Expression of galanin and galanin receptor-1 in normal bone and during fracture repair in the rat (2003) Bone, 33, pp. 788-797; Pacifici, R., Cytokines, estrogen, and postmenopausal osteoporosis - The second decade (1998) Endocrinology, 139, pp. 2659-2661; You, L., Temiyasathit, S., Lee, P., Kim, C.H., Tummala, P., Yao, W., Kingery, W., Jacobs, C.R., Osteocytes as mechanosensors in the inhibition of bone resorption due to mechanical loading (2008) Bone, 42, pp. 172-179; Lerner, U.H., The role of skeletal nerve fibers in bone metabolism (2000) Endocrinologist, 10, pp. 377-382; Sherman, M.S., The nerves of bone (1963) J Bone Joint Surg Am, 45, pp. 522-528; Kuntz, A., Richins, C.A., Innervation of the bone marrow (1945) J Comp Neurol, 83, pp. 213-222; Miller, M.R., Kasahara, M., Observations on innervation of human long bones (1963) Anat Rec, 145, pp. 13-23; Thurston, T.J., Distribution of nerves in long bones as shown by silver impregnation (1982) J Anat, 134, pp. 719-728; Calvo, W., Fortezav, J., On development of bone marrow innervation in new-born rats as studied with silver impregnation and electron microscopy (1969) Am J Anat, 126, pp. 355-371; Sisask, G., Bjurholm, A., Ahmed, M., Kreicbergs, A., The development of autonomic innervation in bone and joints of the rat (1996) J Auton Nerv Syst, 59, pp. 27-33; Gajda, M., Litwin, J.A., Cichocki, T., Timmermans, J.P., Adriaensen, D., Development of sensory innervation in rat tibia: Co-localization of CGRP and substance P with growth-associated protein 43 (GAP-43) (2005) J Anat, 207, pp. 135-144; Jackman, A., Fitzgerald, M., Development of peripheral hindlimb and central spinal cord innervation by subpopulations of dorsal root ganglion cells in the embryonic rat (2000) J Comp Neurol, 418, pp. 281-298; Kosaras, B., Jakubowski, M., Kainz, V., Burstein, R., Sensory innervation of the calvarial bones of the mouse (2009) J Comp Neurol, 515, pp. 331-348; Jones, K.B., Mollano, A.V., Morcuende, J.A., Cooper, R.R., Saltzman, C.L., Bone and brain: A review of neural, hormonal, and musculoskeletal connections (2004) Iowa Orthop J, 24, pp. 123-132; Alberius, P., Skagerberg, G., Adrenergic innervation of the calvarium of the neonatal rat. Its relationship to the sagittal suture and developing parietal bones (1990) Anat Embryol (Berl), 182, pp. 493-498; Herskovits, M.S., Hallas, B.H., Singh, I.J., Study of sympathetic innervation of cranial bones by axonal transport of horseradish peroxidase in the rat: Preliminary findings (1993) Acta Anat (Basel), 147, pp. 178-183; Hill, E.L., Elde, R., Distribution of CGRP-, VIP-, D beta H-, SP-, and NPY-immunoreactive nerves in the periosteum of the rat (1991) Cell Tissue Res, 264, pp. 469-480; Kruger, L., Silverman, J.D., Mantyh, P.W., Sternini, C., Brecha, N.C., Peripheral patterns of calcitonin-gene-related peptide general somatic sensory innervation: Cutaneous and deep terminations (1989) J Comp Neurol, 280, pp. 291-302; Silverman, J.D., Kruger, L., Calcitonin-gene-related-peptide-immunoreactive innervation of the rat head with emphasis on specialized sensory structures (1989) J Comp Neurol, 280, pp. 303-330; Ducy, P., Amling, M., Takeda, S., Priemel, M., Schilling, A.F., Beil, F.T., Shen, J., Karsenty, G., Leptin inhibits bone formation through a hypothalamic relay: A central control of bone mass (2000) Cell, 100, pp. 197-207; Robertson, S.A., Leinninger, G.M., Myers, Jr.M.G., Molecular and neural mediators of leptin action (2008) Physiol Behav, 94, pp. 637-642; Ahima, R.S., Flier, J.S., Leptin (2000) Annu Rev Physiol, 62, pp. 413-437; Tartaglia, L.A., Dembski, M., Weng, X., Deng, N., Culpepper, J., Devos, R., Richards, G.J., Deeds, J., Identification and expression cloning of a leptin receptor, OB-R (1995) Cell, 83, pp. 1263-1271; Zhang, Y., Proenca, R., Maffei, M., Barone, M., Leopold, L., Friedman, J.M., Positional cloning of the mouse obese gene and its human homologue (1994) Nature, 372, pp. 425-432; Takeda, S., Elefteriou, F., Levasseur, R., Liu, X., Zhao, L., Parker, K.L., Armstrong, D., Karsenty, G., Leptin regulates bone formation via the sympathetic nervous system (2002) Cell, 111, pp. 305-317; Stephens, T.W., Basinski, M., Bristow, P.K., Bue-Valleskey, J.M., Burgett, S.G., Craft, L., Hale, J., Kriauciunas, A., The role of neuropeptide y in the antiobesity action of the obese gene product (1995) Nature, 377, pp. 530-532; Chronwall, B.M., Dimaggio, D.A., Massari, V.J., Pickel, V.M., Ruggiero, D.A., O'Donohue, T.L., The anatomy of neuropeptide-Y-containing neurons in rat brain (1985) Neuroscience, 15, pp. 1159-1181; Tatemoto, K., Carlquist, M., Mutt, V., Neuropeptide y - A novel brain peptide with structural similarities to peptide YY and pancreatic polypeptide (1982) Nature, 296, pp. 659-660; Pedrazzini, T., Pralong, F., Grouzmann, E., Neuropeptide Y: The universal soldier (2003) Cell Mol Life Sci, 60, pp. 350-377; Erickson, J.C., Hollopeter, G., Palmiter, R.D., Attenuation of the obesity syndrome of ob/ob mice by the loss of neuropeptide y (1996) Science, 274, pp. 1704-1707; Allison, S.J., Baldock, P.A., Herzog, H., The control of bone remodeling by neuropeptide y receptors (2007) Peptides, 28, pp. 320-325; Bjurholm, A., Kreicbergs, A., Terenius, L., Goldstein, M., Schultzberg, M., Neuropeptide Y-, tyrosine hydroxylase- and vasoactive intestinal polypeptide-immunoreactive nerves in bone and surrounding tissues (1988) J Auton Nerv Syst, 25, pp. 119-125; Ahmed, M., Bjurholm, A., Kreicbergs, A., Schultzberg, M., Neuropeptide Y, tyrosine hydroxylase and vasoactive intestinal polypeptide-immunoreactive nerve fibers in the vertebral bodies, discs, dura mater, and spinal ligaments of the rat lumbar spine (1993) Spine, 18, pp. 268-273; Hill, E.L., Turner, R., Elde, R., Effects of neonatal sympathectomy and capsaicin treatment on bone remodeling in rats (1991) Neuroscience, 44, pp. 747-755; Lindblad, B.E., Nielsen, L.B., Jespersen, S.M., Bjurholm, A., Bunger, C., Hansen, E.S., Vasoconstrictive action of neuropeptide y in bone. The porcine tibia perfused in vivo (1994) Acta Orthop Scand, 65, pp. 629-634; Ahmad, T., Ugarph-Morawski, A., Li, J., Bileviciute-Ljungar, I., Finn, A., Ostenson, C.G., Kreicbergs, A., Bone and joint neuropathy in rats with type-2 diabetes (2004) Regul Pept, 119, pp. 61-67; Ericsson, A., Schalling, M., McIntyre, K.R., Lundberg, J.M., Larhammar, D., Seroogy, K., Hokfelt, T., Persson, H., Detection of neuropeptide y and its mRNA in megakaryocytes: Enhanced levels in certain autoimmune mice (1987) Proc Natl Acad Sci USA, 84, pp. 5585-5589; Ahmed, M., Srinivasan, G.R., Theodorsson, E., Bjurholm, A., Kreicbergs, A., Extraction and quantitation of neuropeptides in bone by radioimmunoassay (1994) Regul Pept, 51, pp. 179-188; Bjurholm, A., Neuroendocrine peptides in bone (1991) Int Orthop, 15, pp. 325-329; Bjurholm, A., Kreicbergs, A., Schultzberg, M., Lerner, U.H., Neuroendocrine regulation of cyclic AMP formation in osteoblastic cell lines (UMR-106-01, ROS 17/2.8, MC3T3-E1, and Saos-2) and primary bone cells (1992) J Bone Miner Res, 7, pp. 1011-1019; Lundberg, P., Allison, S.J., Lee, N.J., Baldock, P.A., Brouard, N., Rost, S., Enriquez, R.F., Simmons, P., Greater bone formation of Y2 knockout mice is associated with increased osteoprogenitor numbers and altered Y1 receptor expression (2007) J Biol Chem, 282, pp. 19082-19091; Nakamura, M., Sakanaka, C., Aoki, Y., Ogasawara, H., Tsuji, T., Kodama, H., Matsumoto, T., Noma, M., Identification of two isoforms of mouse neuropeptide Y-Y1 receptor generated by alternative splicing. Isolation, genomic structure, and functional expression of the receptors (1995) J Biol Chem, 270, pp. 30102-30110; Togari, A., Arai, M., Mizutani, S., Koshihara, Y., Nagatsu, T., Expression of mRNAs for neuropeptide receptors and beta-adrenergic receptors in human osteoblasts and human osteogenic sarcoma cells (1997) Neurosci Lett, 233, pp. 125-128; Igwe, J.C., Jiang, X., Paic, F., Ma, L., Adams, D.J., Baldock, P.A., Pilbeam, C.C., Kalajzic, I., Neuropeptide y is expressed by osteocytes and can inhibit osteoblastic activity (2009) J Cell Biochem, 108, pp. 621-630; Nunes, A.F., Liz, M.A., Franquinho, F., Teixeira, L., Sousa, V., Chenu, C., Lamghari, M., Sousa, M.M., Neuropeptide y expression and function during osteoblast differentiation - Insights from transthyretin knockout mice (2010) FEBS J, 277, pp. 263-275; Baldock, P.A., Sainsbury, A., Couzens, M., Enriquez, R.F., Thomas, G.P., Gardiner, E.M., Herzog, H., Hypothalamic Y2 receptors regulate bone formation (2002) J Clin Invest, 109, pp. 915-921; Ducy, P., Schinke, T., Karsenty, G., The osteoblast: A sophisticated fibroblast under central surveillance (2000) Science, 289, pp. 1501-1504; Allison, S.J., Baldock, P., Sainsbury, A., Enriquez, R., Lee, N.J., Lin, E.J., Klugmann, M., Li, M., Conditional deletion of hypothalamic Y2 receptors reverts gonadectomy-induced bone loss in adult mice (2006) J Biol Chem, 281, pp. 23436-23444; Clegg, D.J., Brown, L.M., Zigman, J.M., Kemp, C.J., Strader, A.D., Benoit, S.C., Woods, S.C., Geary, N., Estradiol-dependent decrease in the orexigenic potency of ghrelin in female rats (2007) Diabetes, 56, pp. 1051-1058; Zengin, A., Zhang, L., Herzog, H., Baldock, P.A., Sainsbury, A., Neuropeptide y and sex hormone interactions in humoral and neuronal regulation of bone and fat (2010) Trends Endocrinol Metab, 21, pp. 411-418; Hosaka, H., Nagata, A., Yoshida, T., Shibata, T., Nagao, T., Tanaka, T., Saito, Y., Tatsuno, I., Pancreatic polypeptide is secreted from and controls differentiation through its specific receptors in osteoblastic MC3T3-E1 cells (2008) Peptides, 29, pp. 1390-1395; Teixeira, L., Sousa, D.M., Nunes, A.F., Sousa, M.M., Herzog, H., Lamghari, M., NPY revealed as a critical modulator of osteoblast function in vitro: New insights into the role of Y1 and Y2 receptors (2009) J Cell Biochem, 107, pp. 908-916; Sainsbury, A., Schwarzer, C., Couzens, M., Herzog, H., Y2 receptor deletion attenuates the type 2 diabetic syndrome of ob/ob mice (2002) Diabetes, 51, pp. 3420-3427; Wilding, J.P., Gilbey, S.G., Bailey, C.J., Batt, R.A., Williams, G., Ghatei, M.A., Bloom, S.R., Increased neuropeptide-Y messenger ribonucleic acid (mRNA) and decreased neurotensin mRNA in the hypothalamus of the obese (ob/ob) mouse (1993) Endocrinology, 132, pp. 1939-1944; Baldock, P.A., Allison, S., McDonald, M.M., Sainsbury, A., Enriquez, R.F., Little, D.G., Eisman, J.A., Herzog, H., Hypothalamic regulation of cortical bone mass: Opposing activity of Y2 receptor and leptin pathways (2006) J Bone Miner Res, 21, pp. 1600-1607; Baldock, P.A., Sainsbury, A., Allison, S., Lin, E.J., Couzens, M., Boey, D., Enriquez, R., Gardiner, E.M., Hypothalamic control of bone formation: Distinct actions of leptin and y2 receptor pathways (2005) J Bone Miner Res, 20, pp. 1851-1857; Baldock, P.A., Allison, S.J., Lundberg, P., Lee, N.J., Slack, K., Lin, E.J., Enriquez, R.F., During, M.J., Novel role of Y1 receptors in the coordinated regulation of bone and energy homeostasis (2007) J Biol Chem, 282, pp. 19092-19102; Lee, N.J., Doyle, K.L., Sainsbury, A., Enriquez, R.F., Hort, Y.J., Riepler, S.J., Baldock, P.A., Herzog, H., Critical role for Y1 receptors in mesenchymal progenitor cell differentiation and osteoblast activity (2010) J Bone Miner Res, , doi:; Allison, S.J., Baldock, P.A., Enriquez, R.F., Lin, E., During, M., Gardiner, E.M., Eisman, J.A., Herzog, H., Critical interplay between neuropeptide y and sex steroid pathways in bone and adipose tissue homeostasis (2009) J Bone Miner Res, 24, pp. 294-304; Sainsbury, A., Baldock, P.A., Schwarzer, C., Ueno, N., Enriquez, R.F., Couzens, M., Inui, A., Gardiner, E.M., Synergistic effects of Y2 and Y4 receptors on adiposity and bone mass revealed in double knockout mice (2003) Mol Cell Biol, 23, pp. 5225-5233; Elefteriou, F., Takeda, S., Liu, X., Armstrong, D., Karsenty, G., Monosodium glutamate-sensitive hypothalamic neurons contribute to the control of bone mass (2003) Endocrinology, 144, pp. 3842-3847; Baldock, P.A., Lee, N.J., Driessler, F., Lin, S., Allison, S., Stehrer, B., Lin, E.J., Wong, I.P., Neuropeptide y knockout mice reveal a central role of NPY in the coordination of bone mass to body weight (2009) PLoS ONE, 4, p. 8415; Sainsbury, A., Cusin, I., Doyle, P., Rohner-Jeanrenaud, F., Jeanrenaud, B., Intracerebroventricular administration of neuropeptide y to normal rats increases obese gene expression in white adipose tissue (1996) Diabetologia, 39, pp. 353-356; Sainsbury, A., Herzog, H., Inhibitory effects of central neuropeptide y on the somatotropic and gonadotropic axes in male rats are independent of adrenal hormones (2001) Peptides, 22, pp. 467-471; Nunes, A.F., Saraiva, M.J., Sousa, M.M., Transthyretin knockouts are a new mouse model for increased neuropeptide y (2006) FASEB J, 20, pp. 166-168; Prigge, S.T., Mains, R.E., Eipper, B.A., Amzel, L.M., New insights into copper monooxygenases and peptide amidation: Structure, mechanism and function (2000) Cell Mol Life Sci, 57, pp. 1236-1259; Eipper, B.A., Stoffers, D.A., Mains, R.E., The biosynthesis of neuropeptides: Peptide alpha-amidation (1992) Annu Rev Neurosci, 15, pp. 57-85; Marques, F., Sousa, J.C., Oliveira, P., Oliveira, H.C., Palha, J.A., The absence of transthyretin does not impair regulation of lipid and glucose metabolism (2007) Horm Metab Res, 39, pp. 529-533
Keywords: Animals; Bone and Bones; bone cell; bone innervation; bone mass; cell differentiation; Homeostasis; Humans; immunoreactivity; leptin; Nerve Net; neuropeptide Y; neuropeptide Y receptor; neuropeptide Y2 receptor; nonhuman; NPY; NPY receptors; osteoblast; Osteoblasts; phenotype; priority journal; protein expression; protein interaction; Protein Isoforms; Receptors, Neuropeptide Y; review

Neuropeptide y expression and function during osteoblast differentiation - Insights from transthyretin knockout mice - Nunes, A.F.; Liz, M.A.; Franquinho, F.; Teixeira, L.; Sousa, V.; Chenu, C.; Lamghari, M.; Sousa, M.M. (FEBS JournalFEBS J., 2010)
To better understand the role of neuropeptide Y (NPY) in bone homeostasis, as its function in the regulation of bone mass is unclear, we assessed its expression in this tissue. By immunohistochemistry, we demonstrated, both at embryonic stages and in the adult, that NPY is synthesized by osteoblasts, osteocytes, and chondrocytes. Moreover, peptidylglycine α-amidating monooxygenase, the enzyme responsible for NPY activation by amidation, was also expressed in these cell types. Using transthyretin (TTR) KO mice as a model of augmented NPY levels, we showed that this strain has increased NPY content in the bone, further validating the expression of this neuropeptide by bone cells. Moreover, the higher amidated neuropeptide levels in TTR KO mice were related to increased bone mineral density and trabecular volume. Additionally, RT-PCR analysis established that NPY is not only expressed in MC3T3-E1 osteoblastic cells and bone marrow stromal cells (BMSCs), but is also detectable by RIA in BMSCs undergoing osteoblastic differentiation. In agreement with our in vivo observations, in vitro, TTR KO BMSCs differentiated in osteoblasts had increased NPY levels and exhibited enhanced competence in undergoing osteoblastic differentiation. In summary, this work contributes to a better understanding of the role of NPY in the regulation of bone formation by showing that this neuropeptide is expressed in bone cells and that increased amidated neuropeptide content is related to increased bone mass. © 2009 FEBS.
Cited By (since 1996): 5Export Date: 21 November 2012Source: Scopusdoi: 10.1111/j.1742-4658.2009.07482.xPubMed ID: 19954489Language of Original Document: EnglishCorrespondence Address: Sousa, M. M.; IBMC, Rua Campo Alegre 823, 4150-180 Porto, Portugal; email: msousa@ibmc.up.ptChemicals/CAS: neuropeptide Y, 82785-45-3, 83589-17-7; Amides; DNA Primers; Neuropeptide Y; Prealbumin; RNA, MessengerReferences: McDonald, A.C., Schuijers, J.A., Shen, P.J., Gundlach, A.L., Grills, B.L., Expression of galanin and galanin receptor-1 in normal bone and during fracture repair in the rat (2003) Bone, 33, pp. 788-797;Pacifici, R., Cytokines, estrogen, and postmenopausal osteoporosis - The second decade (1998) Endocrinology, 139, pp. 2659-2661; You, L., Temiyasathit, S., Lee, P., Kim, C.H., Tummala, P., Yao, W., Kingery, W., Jacobs, C.R., Osteocytes as mechanosensors in the inhibition of bone resorption due to mechanical loading (2008) Bone, 42, pp. 172-179; Chenu, C., Marenzana, M., Sympathetic nervous system and bone remodeling (2005) Joint Bone Spine, 72 (6), pp. 481-483. , DOI 10.1016/j.jbspin.2005.10.007, PII S1297319X05001661; Baldock, P.A., Sainsbury, A., Couzens, M., Enriquez, R.F., Thomas, G.P., Gardiner, E.M., Herzog, H., Hypothalamic Y2 receptors regulate bone formation (2002) J Clin Invest, 109, pp. 915-921; Baldock, P.A., Allison, S.J., Lundberg, P., Lee, N.J., Slack, K., Lin, E.J., Enriquez, R.F., During, M.J., Novel role of Y1 receptors in the coordinated regulation of bone and energy homeostasis (2007) J Biol Chem, 282, pp. 19092-19102; Ducy, P., Amling, M., Takeda, S., Priemel, M., Schilling, A.F., Beil, F.T., Shen, J., Karsenty, G., Leptin inhibits bone formation through a hypothalamic relay: A central control of bone mass (2000) Cell, 100, pp. 197-207; Elefteriou, F., Takeda, S., Liu, X., Armstrong, D., Karsenty, G., Monosodium glutamate-sensitive hypothalamic neurons contribute to the control of bone mass (2003) Endocrinology, 144, pp. 3842-3847; Elefteriou, F., Neuronal signaling and the regulation of bone remodeling (2005) Cell Mol Life Sci, 62, pp. 2339-2349; Bjurholm, A., Kreicbergs, A., Terenius, L., Goldstein, M., Schultzberg, M., Neuropeptide Y-, tyrosine hydroxylase- and vasoactive intestinal polypeptide-immunoreactive nerves in bone and surrounding tissues (1988) J Auton Nerv Syst, 25, pp. 119-125; Hill, E.L., Elde, R., Distribution of CGRP-, VIP-, D beta H-, SP-, and NPY-immunoreactive nerves in the periosteum of the rat (1991) Cell Tissue Res, 264, pp. 469-480; Tabarowski, Z., Gibson-Berry, K., Felten, S.Y., Noradrenergic and peptidergic innervation of the mouse femur bone marrow (1996) Acta Histochem, 98, pp. 453-457; Ahmed, M., Srinivasan, G.R., Theodorsson, E., Bjurholm, A., Kreicbergs, A., Extraction and quantitation of neuropeptides in bone by radioimmunoassay (1994) Regul Pept, 51, pp. 179-188; Ericsson, A., Schalling, M., McIntyre, K.R., Lundberg, J.M., Larhammar, D., Seroogy, K., Hokfelt, T., Persson, H., Detection of neuropeptide y and its mRNA in megakaryocytes: Enhanced levels in certain autoimmune mice (1987) Proc Natl Acad Sci USA, 84, pp. 5585-5589; Lundberg, P., Allison, S.J., Lee, N.J., Baldock, P.A., Brouard, N., Rost, S., Enriquez, R.F., Simmons, P., Greater bone formation of y2 knockout mice is associated with increased osteoprogenitor numbers and altered y1 receptor expression (2007) J Biol Chem, 282, pp. 19082-19091; Stephens, T.W., Basinski, M., Bristow, P.K., Bue-Valleskey, J.M., Burgett, S.G., Craft, L., Hale, J., Kriauciunas, A., The role of neuropeptide y in the antiobesity action of the obese gene product (1995) Nature, 377, pp. 530-532; Baldock, P.A., Sainsbury, A., Allison, S., Lin, E.J., Couzens, M., Boey, D., Enriquez, R., Gardiner, E.M., Hypothalamic control of bone formation: Distinct actions of leptin and y2 receptor pathways (2005) J Bone Miner Res, 20, pp. 1851-1857; Allison, S., Baldock, P., Enriquez, R., Lin, E., During, M., Gardiner, E., Eisman, J., Herzog, H., Critical interplay between neuropeptide y and sex steroid pathways in bone and adipose tissue homeostasis (2008) J Bone Miner Res, 24, pp. 294-304; Nunes, A.F., Saraiva, M.J., Sousa, M.M., Transthyretin knockouts are a new mouse model for increased neuropeptide y (2006) FASEB J, 20, pp. 166-168; Mains, R.E., Cullen, E.I., May, V., Eipper, B.A., The role of secretory granules in peptide biosynthesis (1987) Ann NY Acad Sci, 493, pp. 278-291; Prigge, S.T., Mains, R.E., Eipper, B.A., Amzel, L.M., New insights into copper monooxygenases and peptide amidation: Structure, mechanism and function (2000) Cell Mol Life Sci, 57, pp. 1236-1259; Eipper, B.A., Stoffers, D.A., Mains, R.E., The biosynthesis of neuropeptides: Peptide alpha-amidation (1992) Annu Rev Neurosci, 15, pp. 57-85; Teixeira, L., Sousa, D.M., Nunes, A.F., Sousa, M.M., Herzog, H., Lamghari, M., NPY revealed as a critical modulator of osteoblast function in vitro: New insights into the role of Y1 and Y2 receptors (2009) J Cell Biochem, 107, pp. 908-916; Amano, S., Arai, M., Goto, S., Togari, A., Inhibitory effect of NPY on isoprenaline-induced osteoclastogenesis in mouse bone marrow cells (2007) Biochim Biophys Acta, 1770, pp. 966-973; Baldock, P.A., Allison, S., McDonald, M.M., Sainsbury, A., Enriquez, R.F., Little, D.G., Eisman, J.A., Herzog, H., Hypothalamic regulation of cortical bone mass: Opposing activity of Y2 receptor and leptin pathways (2006) J Bone Miner Res, 21, pp. 1600-1607; Saper, C.B., Loewy, A.D., Swanson, L.W., Cowan, W.M., Direct hypothalamo-autonomic connections (1976) Brain Res, 117, pp. 305-312; Navia, J.M., Harris, S.S., Vitamin A influence on calcium metabolism and calcification (1980) Ann NY Acad Sci, 355, pp. 45-57; Wang, A., Ding, X., Sheng, S., Yao, Z., Retinoic acid inhibits osteogenic differentiation of rat bone marrow stromal cells (2008) Biochem Biophys Res Commun, 375, pp. 435-439; Takahashi, T., Kamiya, N., Kawabata, N., Takagi, M., The effect of retinoic acid on a zinc finger transcription factor, AJ18, during differentiation of a rat clonal preosteoblastic cell line, ROB-C20, into osteoblasts (2008) Arch Oral Biol, 53, pp. 87-94; Grouzmann, E., Comoy, E., Walker, P., Burnier, M., Bohuon, C., Waeber, B., Brunner, H., Production and characterization of four anti-neuropeptide y monoclonal antibodies (1992) Hybridoma, 11, pp. 409-424; Wei, S., Episkopou, V., Piantedosi, R., Maeda, S., Shimada, K., Gottesman, M.E., Blaner, W.S., Studies on the metabolism of retinol and retinol-binding protein in transthyretin-deficient mice produced by homologous recombination (1995) J Biol Chem, 270, pp. 866-870; Karga, H., Papapetrou, P.D., Korakovouni, A., Papandroulaki, F., Polymeris, A., Pampouras, G., Bone mineral density in hyperthyroidism (2004) Clin Endocrinol, 61, pp. 466-472; Episkopou, V., Maeda, S., Nishiguchi, S., Shimada, K., Gaitanaris, G.A., Gottesman, M.E., Robertson, E.J., Disruption of the transthyretin gene results in mice with depressed levels of plasma retinol and thyroid hormone (1993) Proc Natl Acad Sci USA, 90, pp. 2375-2379; Palha, J.A., Episkopou, V., Maeda, S., Shimada, K., Gottesman, M.E., Saraiva, M.J., Thyroid hormone metabolism in a transthyretin-null mouse strain (1994) J Biol Chem, 269, pp. 33135-33139; Palha, J.A., Hays, M.T., Morreale De Escobar, G., Episkopou, V., Gottesman, M.E., Saraiva, M.J., Transthyretin is not essential for thyroxine to reach the brain and other tissues in transthyretin-null mice (1997) Am J Physiol, 272, pp. 485-E493; Palha, J.A., Fernandes, R., De Escobar, G.M., Episkopou, V., Gottesman, M., Saraiva, M.J., Transthyretin regulates thyroid hormone levels in the choroid plexus, but not in the brain parenchyma: Study in a transthyretin-null mouse model (2000) Endocrinology, 141, pp. 3267-3272; Kingery, W.S., Offley, S.C., Guo, T.Z., Davies, M.F., Clark, J.D., Jacobs, C.R., A substance P receptor (NK1) antagonist enhances the widespread osteoporotic effects of sciatic nerve section (2003) Bone, 33, pp. 927-936; Hosaka, H., Nagata, A., Yoshida, T., Shibata, T., Nagao, T., Tanaka, T., Saito, Y., Tatsuno, I., Pancreatic polypeptide is secreted from and controls differentiation through its specific receptors in osteoblastic MC3T3-E1 cells (2008) Peptides, 29, pp. 1390-1395; Fleming, C.E., Saraiva, M.J., Sousa, M.M., Transthyretin enhances nerve regeneration (2007) J Neurochem, 103, pp. 831-839; Sainsbury, A., Cusin, I., Doyle, P., Rohner-Jeanrenaud, F., Jeanrenaud, B., Intracerebroventricular administration of neuropeptide y to normal rats increases obese gene expression in white adipose tissue (1996) Diabetologia, 39, pp. 353-356; Sainsbury, A., Herzog, H., Inhibitory effects of central neuropeptide y on the somatotropic and gonadotropic axes in male rats are independent of adrenal hormones (2001) Peptides, 22, pp. 467-471; Marques, F., Sousa, J.C., Oliveira, P., Oliveira, H.C., Palha, J.A., The absence of transthyretin does not impair regulation of lipid and glucose metabolism (2007) Horm Metab Res, 39, pp. 529-533; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Salingcarnboriboon, R., Tsuji, K., Komori, T., Nakashima, K., Ezura, Y., Noda, M., Runx2 is a target of mechanical unloading to alter osteoblastic activity and bone formation in vivo (2006) Endocrinology, 147, pp. 2296-2305
Keywords: 3T3 Cells; alpha amidating enzyme; Amidated neuropeptide; amidation; Amides; animal cell; animal tissue; Animals; article; Base Sequence; Bone Density; bone development; bone marrow cell; Bone Marrow Cells; Bone marrow stromal cells; bone mass; cartilage cell; cell differentiation; Cells, Cultured; Chondrocytes; controlled study; developmental stage; DNA Primers; embryo; embryo development; Homeostasis; immunohistochemistry; male; Mice; Mice, Knockout; mouse; Mus; neuropeptide Y; nonhuman; NPY; ossification; osteoblast; Osteoblastic differentiation; Osteoblasts; osteocyte; Osteocytes; peptide synthesis; prealbumin; priority journal; protein expression; protein function; radioimmunoassay; regulatory mechanism; reverse transcription polymerase chain reaction; RNA, Messenger; stroma cell; Stromal Cells; trabecular bone

Receptor-mediated gene delivery using PAMAM dendrimers conjugated with peptides recognized by mesenchymal stem cells - Santos, J.L.; Pandita, D.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Balian, G.; Tomás, H. (Molecular PharmaceuticsMol. Pharm., 2010)
As mesenchymal stem cells (MSCs) can differentiate into multiple cell types, the delivery of exogenous genes to this type of cell can be an important tool in tissue regeneration and engineering. However transfection of MSCs using nonviral gene delivery vectors is difficult, the development of more efficient and safe DNA vehicles being necessary. Moreover, specific transfection of MSCs may be required to avoid unwanted side effects in other tissues. In this study, a novel family of gene delivery vectors based on poly(amidoamine) (PAMAM) dendrimers functionalized with peptides displaying high affinity toward MSCs was prepared. The vectors were characterized with respect to their ability to neutralize, bind and compact plasmid DNA (pDNA). The complexes formed between the vectors and pDNA were analyzed concerning their size, -potential, capacity of being internalized by cells and transfection efficiency. These new vectors exhibited low cytotoxicity, receptor-mediated gene delivery into MSCs and transfection efficiencies superior to those presented by native dendrimers and by partially degraded dendrimers. © 2010 American Chemical Society.
Cited By (since 1996): 17Export Date: 21 November 2012Source: Scopusdoi: 10.1021/mp9002877PubMed ID: 20230026Language of Original Document: EnglishCorrespondence Address: Balian, G.; Orthopaedic Research Laboratories, Department of Orthopaedics and Biochemistry and Molecular Genetics, University of Virginia Health System, Charlottesville, VA 22908, United States; email: lenat@uma.ptChemicals/CAS: Dendrimers; Green Fluorescent Proteins, 147336-22-9; PAMAM Starburst; Peptides; enhanced green fluorescent proteinReferences: Väänänen, H.K., Mesenchymal stem cells (2005) Ann. Med., 37, pp. 469-479;Caplan, A.I., Adult mesenchymal stem cells for tissue engineering versus regenerative medicine (2007) J. Cell Physiol., 213, pp. 341-347; Kay, M.A., Glorioso, J.C., Naldini, L., Viral vectors for gene therapy: The art of turning infectious agents into vehicles of therapeutics (2001) Nat. Med., 7, pp. 33-40; Mastrobattista, E., Bravo, S.A., Van Der Aa, M., Crommelin, D.J.A., Nonviral gene delivery systems: From simple transfection agents to artificial viruses (2005) Drug Discovery Today: Technol., 2, pp. 103-109; Merdan, T., Kopecek, J., Kissel, T., Prospects for cationic polymers in gene and oligonucleotide therapy against cancer (2002) Adv. Drug Delivery Rev., 54, pp. 715-758; Hamm, A., Krott, N., Breibach, I., Blindt, R., Bosserhoff, A.K., Efficient transfection method for primary cells (2002) Tissue Eng., 8, pp. 235-245; McMahon, J.M., Conroy, S., Lyons, M., Greiser, U., O'Shea, C., Strappe, P., Howard, L., O'Brien, T., Gene transfer into rat mesenchymal stem cells: A comparative study of viral and nonviral vectors (2006) Stem Cells Dev., 15, pp. 87-96; Svenson, S., Tomalia, D.A., Dendrimers in biomedical applications-reflections on the field (2005) Adv. Drug Delivery Rev., 57, pp. 2106-2129; Duf-s, C., Uchegbu, I.F., Schatzlein, A.G., Dendrimers in gene delivery (2005) Adv. Drug Delivery Rev., 57, pp. 2177-2202; Guillot, M., Eisler, S., Diederich, F., Dendritic vectors for gene transfection (2007) New J. Chem., 31, pp. 1111-1127; Smith, D.K., Dendrimers and the double helix-from DNA binding towards gene therapy (2008) Curr. Top. Med. Chem., 8, pp. 1187-1203; Kukowska-Latallo, J.F., Bielinska, A.U., Johnson, J., Spindler, R., Tomalia, D.A., Baker Jr., J.R., Efficient transfer of genetic material into mammalian cells using Starburst polyamidoamine dendrimers (1996) Proc. Natl. Acad. Sci. U.S.A., 93, pp. 4897-4902; Santos, J.L., Oramas, E., Pêgo, A.P., Granja, P.L., Tomás, H., Osteogenic differentiation of mesenchymal stem cells using PAMAM dendrimers as gene delivery vectors (2009) J. Controlled Release, 134, pp. 141-148; Balian, G., (2008), Bone Targeting Peptides. In United States Patent 7,323,542, issued January 29Snyder, S.L., Sobocinski, P.Z., An improved 2,4,6-trinitrobenzenesulfonic acid method for the determination of amines (1975) Anal. Biochem., 64, pp. 284-288; Haensler, J., Szoka Jr., F.C., Polyamidoamine cascade polymers mediate efficient transfection of cells in culture (1993) Bioconjugate Chem., 4, pp. 372-379; Hosseinkhani, H., Yamamoto, M., Inatsugu, Y., Hiraoka, Y., Inoue, S., Shimokawa, H., Tabata, Y., Enhanced ectopic bone formation using a combination of plasmid DNA impregnation into 3-D scaffold and bioreactor perfusion culture (2006) Biomaterials, 27, pp. 1387-1398; Perrot, S., Dutertre-Catella, H., Martin, C., Rat, P., Warnet, J.M., Resazurin metabolism assay is a new sensitive alternative test in isolated pig cornea (2003) Toxicol. Sci., 72, pp. 122-129; Wood, K.C., Little, S.R., Langer, R., Hammond, P.T., A family of hierarchically self-assembling linear-dendritic hybrid polymers for highly efficient targeted gene delivery (2005) Angew. Chem., Int. Ed., 44, pp. 6704-6708; Dan Luo, K.H., Belcheva, N., Han, E., Mark Saltzman, W., Poly(ethylene glycol)-conjugated PAMAM dendrimer for biocompatible, high-efficiency dna delivery (2002) Macromolecules, 35, pp. 3456-3462; Schaffer, D.V., Lauffenburger, D.A., Optimization of cell surface binding enhances efficiency and specificity of molecular conjugate gene delivery (1998) J. Biol. Chem., 273, pp. 28004-28009; Santos, J.L., Oliveira, H., Pandita, D., Pêgo, A.P., Granja, P.L., Tomás, H., Functionalization of poly(amidoamine) dendrimers with hydrophobic chains for improved gene delivery in mesenchymal stem cells (2010) J. Controlled Release, , doi: 10.1016/j.jconrel.2010.01.034
Keywords: animal cell; animal experiment; animal tissue; Animals; article; asparaginylserylmethionylisoleucylalanylhistidylasparaginyllysylthreonylarginylmethionylhistidylglycylglycylglycylserylcysteine; Cell recognition; cell survival; Cells, Cultured; controlled study; Cytotoxicity; dendrimer; Dendrimers; DNA; DNA binding; Electrophoresis, Agar Gel; flow cytometry; Gene delivery; gene targeting; Gene Transfer Techniques; gene vector; genetic transfection; Genetic Vectors; Green Fluorescent Proteins; male; Mesenchymal stem cell; Mesenchymal Stem Cells; Models, Theoretical; multigene family; nonhuman; PAMAM dendrimers; peptide; Peptides; plasmid DNA; polyamidoamine; priority journal; rat; Rats; Rats, Wistar; serylglycylhistidylglutaminylleucylleucylleucylasparaginyllysylmethionylprolylasparaginylglycylglycylglycylserylcysteine; unclassified drug; Zeta potential

Segmentation of the carotid intima-media region in B-mode ultrasound images - Rocha, R.; Campilho, A.; Silva, J.; Azevedo, E.; Santos, R. (Image and Vision ComputingImage Vision Comput, 2010)
This paper proposes a new approach for the segmentation of both near-end and far-end intima-media regions of the common carotid artery in ultrasound images. The method requires minimal user interaction and is able to segment the near-end wall in arteries with large, hypoechogenic and irregular plaques, issues usually not considered previously due to the increased segmentation difficulty. The adventitia is detected by searching for the best fit of a cubic spline to edges having features compatible with the adventitia boundary. The algorithm uses a global smoothness constraint and integrates discriminating features of the adventitia to reduce the attraction by other edges. Afterwards, using the information of the adventitia location, the lumen boundary is detected by combining dynamic programming, smooth intensity thresholding surfaces and geometric snakes. Smooth contours that correctly adapt to the intima are produced, even in the presence of deep concavities. Moreover, unlike balloon-based snakes, the propagation force does not depend on gradients and does not require a predefined direction. An extensive statistical evaluation is computed, using a set of 47 images from 24 different symptomatic patients, including several classes, sizes and shapes of plaques. Bland-Altman plots of the mean intima-media thickness, for manual segmentations of two medical experts, show a high intra-observer and inter-observer agreement, with mean differences close to zero (mean between -0.10 mm and 0.18 mm) and with the large majority of differences within the limits of agreement (standard deviation between 0.10 mm and 0.12 mm). Similar plots reveal a good agreement between the automatic and the manual segmentations (mean between -0.07 mm and 0.11 mm and standard deviation between 0.11 mm and 0.12 mm). © 2009 Elsevier B.V. All rights reserved.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: IVCODdoi: 10.1016/j.imavis.2009.09.017Language of Original Document: EnglishCorrespondence Address: Rocha, R.; INEB - Inst. de Eng. Biomédica, Divisão de Sinal e Imagem, Campus FEUP, 4200-465 Porto, Portugal; email: rhr@isep.ipp.ptReferences: O'Leary, D., Polak, J., Kronmal, R., Manolio, T., Burke, G., Wolfson Jr., S., Carotid-artery intima and media thickness as a risk factor for myocardial infarction and stroke in older adults (1999) New Engl. J. Med., 340, pp. 14-22;Hodis, H., Mack, W., LaBree, L., Selzer, R., Liu, C., Liu, C., Azen, S., The role of carotid arterial intima-media thickness in predicting clinical coronary events (1998) Ann. Intern. Med., 128 (4), pp. 262-269; Kern, R., Szabo, K., Hennerici, M., Meairs, S., Characterization of carotid artery plaques using real-time compound B-mode ultrasound (2004) Stroke, 35, pp. 870-875; Ellis, S.M., Naoumova, R.P., Neuwirth, C.K., Eckersley, R., Cosgrove, D.O., Thompson, G.R., Sidhu, P.S., Measurement of the reflectivity of the intima-medial layer of the common carotid artery improves the discriminatory value of intima-medial thickness measurement as a predictor of risk of atherosclerotic disease (2007) Ultrasound Med. Biol., 33 (7), pp. 1029-1038; Graf, I.M., Schreuder, F.H.B.M., Hameleers, J.M., Mess, W.H., Reneman, R.S., Hoeks, A.P.G., Wall irregularity rather than intima-media thickness is associated with nearby atherosclerosis (2009) Ultrasound Biol. Med., 35 (6), pp. 955-961; Baldassarre, D., Amato, M., Bondioli, A., Sirtori, C.R., Tremoli, E., Carotid artery intima-media thickness measured by ultrasonography in normal clinical practice correlates well with atherosclerosis risk factors (2000) Stroke, 31, pp. 2426-2430; Halenka, M., Noninvasive measurement of early atherosclerosis by high-resolution B-mode ultrasonography (1999) Acta Univ. Palacki. Olomu. Fac. Med., 142, pp. 7-12; Rocha, R., (2007) Image Segmentation and Reconstruction of 3D Surfaces from Carotid Ultrasound Images, , http://www.ineb.fe.up.pt/bmivic, Ph.D. thesis, Faculdade de Engenharia da Universidade do Porto, Porto July; Gee, A., Prager, R., Treece, G., Berman, L., Engineering a freehand 3D ultrasound system (2003) Pattern Recogn. Lett., 24 (4-5), pp. 757-777; Sonka, M., Liang, W., Stefancik, R., Stolpen, A., Handbook of Medical Imaging: Medical Image Processing and Analysis (2000) SPIE, 2; Yu, Y., Acton, S., Speckle reducing anisotropic diffusion (2002) IEEE Trans. Image Process., 11 (11), pp. 1260-1270; Yu, Y., Acton, S., Edge detection in ultrasound imagery using the instantaneous coefficient of variation (2004) IEEE Trans. Image Process., 13 (12), pp. 1640-1655; Thijssen, J.M., Ultrasonic speckle formation, analysis and processing applied to tissue characterization (2003) Pattern Recogn. Lett., 24 (4-5), pp. 659-675; Loizou, C.P., Pattichis, C.S., Christodoulou, C.I., Istepanian, R.S.H., Pantziaris, M., Nicolaides, A., Comparative evaluation of despeckle filtering in ultrasound imaging of the carotid artery (2005) IEEE Trans. Ultrason. Fer. Freq. Control, 52 (10), pp. 1653-1669; Chan, K.L., Ultrasonic tissue characterization using fractal feature (1993) IEE Conf. Acoustic Sensing and Imaging, 369, pp. 183-188; Touboul, P.J., Prati, P., Scarabin, P.-Y., Adrai, V., Thibout, E., Ducimetiere, P., Use of monitoring software to improve the measurement of carotid wall thickness by B-mode imaging (1992) J. Hypertens., 10 (5), pp. 37-41; Gariepy, J., Massonneau, M., Levenson, J., Heudes, D., Simon, A., the Groupe de prevention cardio-vasculaire en medecine du travail, evidence for in vivo carotid and femoral wall thickness in human hypertension (1993) J. Hypertens., 22 (1), pp. 111-118; Selzer, R.H., Hodis, H.N., Kwong-Fu, H., Mack, W.J., Lee, P.L., Liu, C.R., Liu, C.H., Evaluation of computerized edge tracking for quantifying intima-media thickness of the common carotid artery from B-mode ultrasound images (1994) Atherosclerosis, 111, pp. 1-11; Gustavsson, T., Liang, Q., Wendelhag, I., Wikstrand, J., A dynamic programming procedure for automated ultrasonic measurement of the carotid artery (1994) Comput. Cardiol.; Wendelhag, I., Liang, Q., Gustavsson, T., Wikstrand, J., A new automated computerized analyzing system simplifies readings and reduces the variability in ultrasound measurement of intima-media thickness (1997) Stroke, 28, pp. 2195-2200; Automatic detection of the intimal and the adventitial layers of the common carotid artery wall in ultrasound Bmode images using snakes, in: International Conference on Image Analysis and Processing, B. Werer, 1999, pp. 452-457Liang, Q., Wendelhag, I., Wikstrand, J., Gustavsson, T., A multiscale dynamic programming procedure for boundary detection in ultrasound artery images (2000) IEEE Trans. Med. Imag., 19 (2), pp. 127-142; Selzer, R.H., Mack, W.J., Lee, P.L., Kwong-Fu, H., Hodis, H.N., Improved common carotid elasticity and intima-media thickness measurements from computer analysis of sequential ultrasound frames (2001) Atherosclerosis, 154 (1), pp. 185-193; Schmidt-Trucksass, A., Cheng, D., Sandrock, M., Schulte-Monting, J., Rauramaa, R., Huonker, M., Burkhardt, H., Computerized analysing system using the active contour in ultrasound measurement of carotid artery intima-media thickness (2001) Clin. Physiol., 5, pp. 561-569; Cheng, D., Schmidt-Trucksass, A., Cheng, K., Burkhardt, H., Using snakes to detect the intimal and adventitial layers of the common carotid artery wall in sonographic images (2002) Comput. Methods Programs Biomed., 67, pp. 27-37; Stein, J.H., Korcarz, C.E., Mays, M.E., Douglas, P.S., Palta, M., Zhang, H., LeCaire, T., Fan, L., A semiautomated ultrasound border detection program that facilitates clinical measurement of ultrasound carotid intima-media thickness (2005) J. Am. Soc. Echocardiogr., 18 (3), pp. 244-251; Loizou, C.P., Pattichis, C.S., Pantziaris, M., Tyllis, T., Nicolaides, A., Snakes based segmentation of the common carotid artery intima media (2007) Med. Bio. Eng. Comput., 45, pp. 35-49; Yanowitz, S.D., Bruckstein, A.M., A new method for image segmentation (1989) Comput. Graph. Image Process., 46, pp. 82-95; Chan, T., Vese, L., Active contours without edges (2001) IEEE Trans. Image Process., 10 (2), pp. 266-277; Vese, L.A., Chan, T.F., A multiphase level set framework for image segmentation using the Mumford and Shah model (2002) Int. J. Comput. Vision, 50 (3), pp. 271-293; Fischler, M.A., Bolles, R.C., Random sample consensus: a paradigm for model fitting with applications to image analysis and automated cartography (1981) Commun. ACM, 24 (6), pp. 381-395; Zack, G.W., Rogers, W.E., Latt, S.A., Automatic measurement of sister chromatid exchange frequency (1977) J. Histochem. Cytochem., 25 (7), pp. 741-753; Canny, J., A computational approach to edge detection (1986) IEEE Trans. Pattern Anal. Mach. Intell., 8 (6), pp. 679-698; Rudin, L., Osher, S., Fatemi, E., Nonlinear total variation based noise removal algorithms (1992) Proceedings of the Eleventh Annual International Conference of the Center for Nonlinear Studies on Experimental Mathematics: Computational Issues in Nonlinear Science, pp. 259-268. , Elsevier North-Holland, Inc; Rudin, L., Osher, S., Total variation based image restoration with free local constraints (1994) Proceedings of IEEE International Conference on Image Processing (ICIP'94), 1, pp. 31-35; Sethian, J.A., (1999) Level Set Methods and Fast Marching Methods, , Cambridge University Press; Osher, S., Fedkiw, R., (2003) Level Set Methods and Dynamic Implicit Surfaces, , Springer-Verlag, New York; Mumford, D., Shah, J., Optimal approximations by piecewise smooth functions and associated variational problems (1989) Commun. Pure Appl. Math., 42 (5), pp. 577-685; Burden, R., Faires, J.D., (2000) Numerical Analysis, , Brooks Cole; Breu, H., Gil, J., Kirkpatrick, D., Werman, M., Linear time Euclidean distance transform algorithms (1995) IEEE Trans. Pattern Anal. Mach. Intell., 17 (5), pp. 529-533; Bland, J.M., Altman, D.G., Statistical methods for assessing agreement between two methods of clinical measurement (1986) Lancet, 1 (8476), pp. 307-310; Loizou, C.P., Pattichis, C.S., Pantziaris, M., Nicolaides, A., An integrated system for the segmentation of atherosclerotic carotid plaque (2007) IEEE Trans. Info. Tech. Biomed., 11 (6), pp. 661-667; de Boor, C., (1978) A Practical Guide to Splines, , Springer-Verlag; Unser, M., Splines: a perfect fit for signal and image processing (1999) IEEE Signal Processing Magazine, 16 (6), pp. 22-38; Yang, Z., Tuthill, T.A., Raunig, D.L., Fox, M.D., Analoui, M., Pixel compounding: resolution-enhanced ultrasound imaging for quantitative analysis (2007) Ultrasound Med. Biol., 33 (8), pp. 1309-1319
Keywords: Acoustic waves; B-mode ultrasound images; Best fit; Carotid; Common carotid artery; Cubic spline; Digital image storage; Dynamic programming; Edge detection; End-wall; Function evaluation; Geometric snake; Geometric snakes; Image segmentation; Intima-media thickness; Manual segmentation; Medical experts; New approaches; Smoothness constraints; Standard deviation; Statistical evaluation; statistics; Thresholding; Ultrasonics; Ultrasound image; Ultrasound images; User interaction

Targeted gene delivery into peripheral sensorial neurons mediated by self-assembled vectors composed of poly(ethylene imine) and tetanus toxin fragment c - Oliveira, H.; Fernandez, R.; Pires, L.R.; Martins, M.C.L.; Simões, S.; Barbosa, M.A.; Pêgo, A.P. (Journal of Controlled ReleaseJ. Control. Release, 2010)
A simple, safe and efficient system that can specifically transfect peripheral sensorial neurons can bring new answers to address peripheral neuropathies. A multi-component non-viral gene delivery vector targeted to peripheral nervous system cells was developed, using poly(ethylene imine) (PEI) as starting material. A binary DNA/polymer complex based on thiolated PEI (PEISH) was optimized, considering complex size and zeta potential and the ability to transfect a sensorial neuron cell line (ND7/23). The 50. kDa non-toxic fragment from tetanus toxin (HC), which has been previously shown to interact specifically with peripheral neurons and to undergo retrograde transport, was grafted to the complex core via a bifunctional PEG (HC-PEG) reactive for the thiol moieties present in the complex surface. Several formulations of HC-PEG ternary complexes were tested for targeting, by assessing the extent of cellular internalization and levels of transfection, in both the ND7/23 and NIH 3 T3 (fibroblast) cell lines. Targeted gene transfer to the neuronal cell line was observed for the complex formulations containing 5 and 7.5. Μg of HC-PEG. Finally, our results demonstrate that the developed ternary vectors are able to transfect primary cultures of dorsal root ganglion dissociated neurons in a targeted manner and elicit the expression of a relevant neurotrophic factor. © 2010 Elsevier B.V.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JCREEdoi: 10.1016/j.jconrel.2010.01.018PubMed ID: 20093157Language of Original Document: EnglishCorrespondence Address: Pêgo, A.P.; INEB-Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: apego@ineb.up.ptChemicals/CAS: DNA, 9007-49-2; macrogol, 25322-68-3; polyethyleneimine, 74913-72-7; DNA, 9007-49-2; Imines; Peptide Fragments; Polyethylenes; Tetanus Toxin; poly(ethylene imine); tetanus toxin fragment CReferences: Rodriguez, F.J., Valero-Cabre, A., Navarro, X., Regeneration and functional recovery following peripheral nerve injury (2004) Drug Discov. Today, 1 (2), pp. 177-185;Sahenk, Z., Neurotrophins and peripheral neuropathies (2006) Brain Pathol., 16 (4), pp. 311-319; Apfel, S.C., Kessler, J.A., Neurotrophic factors in the therapy of peripheral neuropathy (1995) Baillieres Clin. Neurol., 4 (3), pp. 593-606; Apfel, S.C., Is the therapeutic application of neurotrophic factors dead? (2002) Ann. Neurol., 51 (1), pp. 8-11; Glorioso, J.C., Mata, M., Fink, D.J., Therapeutic gene transfer to the nervous system using viral vectors (2003) J. Neurovirol., 9 (2), pp. 165-172; Boussif, O., Lezoualc'h, F., Zanta, M.A., Mergny, M.D., Scherman, D., Demeneix, B., A versatile vector for gene and oligonucleotide transfer into cells in culture and in vivo: polyethylenimine (1995) Proc. Natl. Acad. Sci. U.S.A., 92 (16), pp. 7297-7301; Coll, J.L., Chollet, P., Brambilla, E., Desplanques, D., Behr, J.P., Favrot, M., In vivo delivery to tumors of DNA complexed with linear polyethylenimine (1999) Hum. Gene Ther., 10 (10), pp. 1659-1666; Schaffer, D.V., Lauffenburger, D.A., Optimization of cell surface binding enhances efficiency and specificity of molecular conjugate gene delivery (1998) J. Biol. Chem., 273 (43), pp. 28004-28009; Zanta, M.A., Boussif, O., Adib, A., Behr, J.P., In vitro gene delivery to hepatocytes with galactosylated polyethylenimine (1997) Bioconjug. Chem., 8 (6), pp. 839-844; Diebold, S.S., Lehrmann, H., Kursa, M., Wagner, E., Cotten, M., Zenke, M., Efficient gene delivery into human dendritic cells by adenovirus polyethylenimine and mannose polyethylenimine transfection (1999) Hum. Gene Ther., 10 (5), pp. 775-786; Blessing, T., Kursa, M., Holzhauser, R., Kircheis, R., Wagner, E., Different strategies for formation of PEGylated EGF-conjugated PEI/DNA complexes for targeted gene delivery (2001) Bioconjug. Chem., 12 (4), pp. 529-537; Erbacher, P., Remy, J.S., Behr, J.P., Gene transfer with synthetic virus-like particles via the integrin-mediated endocytosis pathway (1999) Gene Ther., 6 (1), pp. 138-145; Kircheis, R., Kichler, A., Wallner, G., Kursa, M., Ogris, M., Felzmann, T., Coupling of cell-binding ligands to polyethylenimine for targeted gene delivery (1997) Gene Ther., 4 (5), pp. 409-418; Park, I.K., Lasiene, J., Chou, S.H., Horner, P.J., Pun, S.H., Neuron-specific delivery of nucleic acids mediated by Tet1-modified poly(ethylenimine) (2007) J. Gene Med., 9 (8), pp. 691-702; Kwon, E.J., Bergen, J.M., Park, I.K., Pun, S.H., Peptide-modified vectors for nucleic acid delivery to neurons (2008) J. Control. Release, 132 (3), pp. 230-235; Price, D.L., Griffin, J., Young, A., Peck, K., Stocks, A., Tetanus toxin: direct evidence for retrograde intraaxonal transport (1975) Science, 188 (4191), pp. 945-947; Figueiredo, D.M., Hallewell, R.A., Chen, L.L., Fairweather, N.F., Dougan, G., Savitt, J.M., Delivery of recombinant tetanus-superoxide dismutase proteins to central nervous system neurons by retrograde axonal transport (1997) Exp. Neurol., 145 (2 PART 1), pp. 546-554; Fishman, P.S., Savitt, J.M., Farrand, D.A., Enhanced CNS uptake of systemically administered proteins through conjugation with tetanus C-fragment (1990) J. Neurol. Sci., 98 (2-3), pp. 311-325; Coen, L., Osta, R., Maury, M., Brulet, P., Construction of hybrid proteins that migrate retrogradely and transynaptically into the central nervous system (1997) Proc. Natl. Acad. Sci. U.S.A., 94 (17), pp. 9400-9405; Knight, A., Carvajal, J., Schneider, H., Coutelle, C., Chamberlain, S., Fairweather, N., Non-viral neuronal gene delivery mediated by the HC fragment of tetanus toxin (1999) Eur. J. Biochem., 259 (3), pp. 762-769; Carlisle, R.C., Etrych, T., Briggs, S.S., Preece, J.A., Ulbrich, K., Seymour, L.W., Polymer-coated polyethylenimine/DNA complexes designed for triggered activation by intracellular reduction (2004) J. Gene Med., 6 (3), pp. 337-344; Goula, D., Remy, J.S., Erbacher, P., Wasowicz, M., Levi, G., Abdallah, B., Size, diffusibility and transfection performance of linear PEI/DNA complexes in the mouse central nervous system (1998) Gene Ther., 5 (5), pp. 712-717; Sinha, K., Box, M., Lalli, G., Schiavo, G., Schneider, H., Groves, M., Analysis of mutants of tetanus toxin Hc fragment: ganglioside binding, cell binding and retrograde axonal transport properties (2000) Mol. Microbiol., 37 (5), pp. 1041-1051; Ellman, G.L., Tissue sulfhydryl groups (1959) Arch. Biochem. Biophys., 82 (1), pp. 70-77; (1993) Iodine-125, a Guide to Radioionation Techniques, , Amersham Life Science; O'brien, J., Wilson, I., Orton, T., Pognan, F., Investigation of the Alamar Blue (resazurin) fluorescent dye for the assessment of mammalian cell cytotoxicity (2000) Eur. J. Biochem., 267 (17), pp. 5421-5426; Pollard, H., Remy, J.S., Loussouarn, G., Demolombe, S., Behr, J.P., Escande, D., Polyethylenimine but not cationic lipids promotes transgene delivery to the nucleus in mammalian cells (1998) J. Biol. Chem., 273 (13), pp. 7507-7511; Neu, M., Fischer, D., Kissel, T., Recent advances in rational gene transfer vector design based on poly(ethylene imine) and its derivatives (2005) J. Gene Med., 7 (8), pp. 992-1009; Moffatt, S., Papasakelariou, C., Wiehle, S., Cristiano, R., Successful in vivo tumor targeting of prostate-specific membrane antigen with a highly efficient J591/PEI/DNA molecular conjugate (2006) Gene Ther., 13 (9), pp. 761-772; Kircheis, R., Ostermann, E., Wolschek, M.F., Lichtenberger, C., Magin-Lachmann, C., Wightman, L., Tumor-targeted gene delivery of tumor necrosis factor-alpha induces tumor necrosis and tumor regression without systemic toxicity (2002) Cancer Gene Ther., 9 (8), pp. 673-680; Bellomo, G., Vairetti, M., Stivala, L., Mirabelli, F., Richelmi, P., Orrenius, S., Demonstration of nuclear compartmentalization of glutathione in hepatocytes (1992) Proc. Natl. Acad. Sci. U.S.A., 89 (10), pp. 4412-4416; Liu, H.S., Jan, M.S., Chou, C.K., Chen, P.H., Ke, N.J., Is green fluorescent protein toxic to the living cells? (1999) Biochem. Biophys. Res. Commun., 260 (3), pp. 712-717; Baens, M., Noels, H., Broeckx, V., Hagens, S., Fevery, S., Billiau, A.D., The dark side of EGFP: defective polyubiquitination (2006) PLoS One, 1, pp. e54; Taghizadeh, R.R., Sherley, J.L., CFP and YFP, but not GFP, provide stable fluorescent marking of rat hepatic adult stem cells (2008) J. Biomed. Biotechnol., 2008. , 453590; Liu, J.K., Tenga, Q.S., Garrity-Moses, M., Federici, T., Tanase, D., Imperiale, M.J., A novel peptide defined through phage display for therapeutic protein and vector neuronal targeting (2005) Neurobiol. Dis., 19 (3), pp. 407-418; Fishman, P.S., Carrigan, D.R., Retrograde transneuronal transfer of the C-fragment of tetanus toxin (1987) Brain Res., 406 (1-2), pp. 275-279
Keywords: Aberrations; animal cell; Animals; article; Bifunctional; Cell culture; Cell Line, Tumor; Cell lines; cell strain 3T3; Cells, Cultured; Cellular internalization; Chemical modification; Complex cores; Complex formulations; Complex surface; controlled study; DNA; DNA protein complex; Dorsal root ganglia; Efficient systems; embryo; Ethylene; Female; Gene transfer; genetic transfection; Imines; internalization; macrogol; Mice; mouse; Multicomponents; nanoparticle; nanoparticles; neuroblastoma cell; Neuronal cell; Neurons; neurotrophic factor; Neurotrophic factors; NIH 3T3 Cells; Nitrogen compounds; Non-viral; Non-viral gene delivery; nonhuman; Nonviral; nonviral gene delivery system; Nucleic acids; Particle Size; Peptide Fragments; Peripheral nervous system; Peripheral neuropathy; Plasmids; Polyethylene Glycols; Polyethylene oxides; Polyethyleneimine; Polyethylenes; Primary culture; priority journal; process optimization; protein expression; rat; Rats; Rats, Wistar; Regenerative Medicine; Self-assembled; sensory nerve cell; spinal ganglion; Starting materials; Targeted; Targeted gene delivery; Ternary complex; Ternary vectors; Tetanus toxin; tetanus toxin fragment c; Transfection; unclassified drug; Zeta potential

TNF-α regulates the effects of irradiation in the mouse bone marrow microenvironment - Cachaço, A.S.; Carvalho, T.; Santos, A.C.; Igreja, C.; Fragoso, R.; Rio, C.O.; Ferreira, M.; Serpa, J.; Correia, S.; Pinto-Do-Ó, P.; Dias, S. (PLoS ONEPLoS ONE, 2010)
Background: Secondary bone marrow (BM) myelodysplastic syndromes (MDS) are increasingly common, as a result of radio or chemotherapy administered to a majority of cancer patients. Patients with secondary MDS have increased BM cell apoptosis, which results in BM dysfunction (cytopenias), and an increased risk of developing fatal acute leukemias. In the present study we asked whether TNF-α, known to regulate cell apoptosis, could modulate the onset of secondary MDS. Principal Findings:We show that TNF-α is induced by irradiation and regulates BM cells apoptosis in vitro and in vivo. In contrast to irradiated wild type (WT) mice, TNF-α deficient (TNF-α KO) mice or WT mice treated with a TNF-α-neutralizing antibody were partially protected from the apoptotic effects of irradiation. Next we established a 3-cycle irradiation protocol, in which mice were sub-lethally irradiated once monthly over a 3 month period. In this model, irradiated WT mice presented loss of microsatellite markers on BM cells, low white blood cell (WBC) counts, reduced megakaryocyte (MK) and platelet levels (thrombocytopenia) and macrocytic anemia, phenoypes that suggest the irradiation protocol resulted in BM dysfunction with clinical features of MDS. In contrast, TNF-α KO mice were protected from the irradiation effects: BM cell apoptosis following irradiation was significantly reduced, concomitant with sustained BM MK numbers and absence of other cytopenias. Moreover, irradiated WT mice with long term (≥5 months) BM dysfunction had increased BM angiogenesis, MMPs and VEGF and NFkB p65, suggestive of disease progression. Conclusion:Taken together, our data shows that TNF-α induction following irradiation modulates BM cell apoptosis and is a crucial event in BM dysfunction, secondary MDS onset and progression. © 2010 Cachaço et al.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusArt. No.: e8980doi: 10.1371/journal.pone.0008980Language of Original Document: EnglishCorrespondence Address: Cachaço, A. S.; Angiogenesis Laboratory, Centro de Investigação em Patobiologia Molecular (CIPM), Instituto Portugues de Oncologia de Francisco Gentil, Lisboa, PortugalChemicals/CAS: vasculotropin, 127464-60-2; vasculotropin A, 489395-96-2; Antibodies, Neutralizing; Matrix Metalloproteinases, 3.4.24.-; Tumor Necrosis Factor-alpha; Vascular Endothelial Growth Factor AReferences: Baud, V., Karin, M., Signal transduction by tumor necrosis factor and its relatives (2001) Trends Cell Biol, 11, pp. 372-377;Balkwill, F., Mantovani, A., Inflammation and cancer: Back to Virchow? (2001) Lancet, 357, pp. 539-345; Lejeune, F.J., Rüegg, C., Recombinant human tumor necrosis factor: An efficient agent for cancer treatment (2006) Bull Cancer, 93 (8), pp. E90-100; Moore, R.J., Owens, D.M., Stamp, G., Arnott, C., Burke, F., Mice deficient in tumor necrosis factor-alpha are resistant to skin carcinogenesis (1999) Nat Med, 5, pp. 828-831; Scott, K.A., Arnott, C.H., Robinson, S.C., Moore, R.J., Thompson, R.G., TNF-alpha regulates epithelial expression of MMP-9 and integrin alphavbeta6 during tumour promotion. A role for TNF-alpha in keratocyte migration? (2004) Oncogene, 23, pp. 6954-6966; Hagemann, T., Robinson, S.C., Schulz, M., Trumper, L., Balkwill, F.R., Enhanced invasiveness of breast cancer cell lines upon co-cultivation with macrophages is due to TNF-alpha dependent up-regulation of matrix metalloproteases (2004) Carcinogenesis, 25 (8), pp. 1543-1549; Yang, W.L., Godwin, A.K., Xu, X.X., Tumor necrosis factor-alpha-induced matrix proteolytic enzyme production and basement membrane remodeling by human ovarian surface epithelial cells: Molecular basis linking ovulation and cancer risk (2004) Cancer Res, 64 (4), pp. 1534-1540; Redondo-Muñoz, J., Escobar-Díaz, E., Samaniego, R., Terol, M.J., García-Marco, J.A., MMP-9 in B-cell chronic lymphocytic leukemia is up-regulated by alpha4beta1 integrin or CXCR4 engagement via distinct signaling pathways, localizes to podosomes, and is involved in cell invasion and migration (2006) Blood, 108 (9), pp. 3143-3151; Rosselli, F., Sancean, J., Gluckman, E., Abnormal lymphokine production: A novel feature of the genetic disease Fanconi anemia. In vitro and in vivo spontaneous overproduction of tumor necrosis factor α (1994) Blood, 83 (5), pp. 1216-1225; Dufour, C., Corcione, A., Svahn, J., Haupt, R., Poggi, V., TNF-alpha and IFN-gamma are overexpressed in the bone marrow of Fanconi anemia patients and TNF-alpha suppresses erythropoiesis in vitro (2003) Blood, 102 (6), pp. 2053-2059; Kuruvilla J, Leitch HA, Vickars LM, Galbraith PF, Li CH, et al. (2003) Aplastic anemia following administration of a tumor necrosis factor-alpha inhibitor. Eur J Haematol 71(5): 396-8. Erratum in: Eur J Haematol. (2004) 72(4):306Hara, T., Ando, K., Tsurumi, H., Moriwaki, H., Excessive production of tumor necrosis factor-alpha by bone marrow T lymphocytes is essential in causing bone marrow failure in patients with aplastic anemia (2004) Eur J Haematol, 73 (1), pp. 10-16; Kerbauy, D.B., Deeg, H.J., Apoptosis and antiapoptotic mechanisms in the progression of myelodysplastic syndromes (2007) Exp Hematol, 35 (11), pp. 1739-1746; Lv, L., Kerzic, P., Lin, G., Schnatter, A.R., Bao, L., The TNF-alpha 238A polymorphism is associated with susceptibility to persistent bone marrow dysplasia following chronic exposure to benzene (2007) Leuk Res, 31 (11), pp. 1479-1485; Boula, A., Voulgarelis, M., Giannouli, S., Katrinakis, G., Psyllaki, M., Effect of cA2 anti.tumor necrosis factor-alpha antibody therapy on hematopoiesis of patients with myelodysplastic syndromes (2006) Clin Cancer Res, 12, pp. 3099-3108; Deeg, H.J., Gotlib, J., Beckham, C., Dugan, K., Holmberg, L., Soluble TNF receptor fusion protein (etanercept) for the treatment of myelodysplastic syndrome: A pilot study (2002) Leukemia, 16 (2), pp. 162-164; Maciejewski JP, Risitano AM, Sloand EM, Wisch L, Geller N, et al. (2002) Br J Haematol 117(1): 119-26. Erratum in: Br J Haematol (2002) 117(4):1002. Ristiano Antonio M [corrected to Risitano Antonio M]De Roos, A.J., Deeg, H.J., Davis, S., A population-based study of survival in patients with secondary myelodysplastic syndromes (MDS): Impact of type and treatment of primary cancers (2007) Cancer Causes Control, 18 (10), pp. 1199-1208; Malcovati, L., Nimer, S.D., Myelodysplastic syndromes: Diagnosis and Staging (2008) Cancer Control, 15 (4 SUPPL.EMENT), pp. 4-13; Haran-Ghera, N., Peled, A., Krautghamer, R., Resnitzky, P., Initiation and promotion in radiation-induced myeloid leukemia (1992) Leukemia, 6 (7), pp. 689-695; Padmanabhan, A., Baker, J.A., Zirpoli, G., Sait, S.N., Ford, L.A., Acute myeloid leukemia and myelodysplastic syndrome following breast cancer: Increased frequency of other cancers and of cancers in multiple family members (2008) Leuk Res, 32 (12), pp. 1820-1823; Zhang, Y., Harada, A., Bluethmann, H., Wang, J.B., Nakao, S., Tumor necrosis factor (TNF) is a physiologic regulator of hematopoietic progenitor cells: Increase of early hematopoietic progenitor cells in TNF receptor p55-deficient mice in vivo and potent inhibition of progenitor cell proliferation by TNF alpha in vitro (1995) Blood, 86 (8), pp. 2930-2937; Rebel, V.I., Hartnett, S., Hill, G.R., Lazo-Kallanian, S.B., Ferrara, J.L., Essential role for the p55 tumor necrosis factor receptor in regulating hematopoiesis at a stem cell level (1999) J Exp Med, 190 (10), pp. 1493-1504; Drutskaya, M.S., Ortiz, M., Liepinsh, D.J., Kuprash, D.V., Nedospasov, S.A., Inhibitory effects of tumor necrosis factor on hematopoiesis seen in vitro are translated to increased numbers of both committed and multipotent progenitors in TNF-deficient mice (2005) Exp Hematol, 33 (11), pp. 1348-1356; Rübe, C.E., Wilfert, F., Uthe, D., Schmid, K.W., Knoop, R., Modulation of radiation-induced tumour necrosis factor alpha (TNF-alpha) expression in the lung tissue by pentoxifylline (2002) Radiother Oncol, 64 (2), pp. 177-187; Zhang, M., Qian, J., Xing, X., Kong, F.M., Zhao, L., Inhibition of the tumor necrosis factor-alpha pathway is radioprotective for the lung (2008) Clin Cancer Res, 14 (6), pp. 1868-1876; Daigle, J.L., Hong, J.H., Chiang, C.S., McBride, W.H., The role of tumor necrosis factor signaling pathways in the response of murine brain to irradiation (2001) Cancer Res, 61 (24), pp. 8859-8865; Dy, L.C., Pei, Y., Travers, J.B., Augmentation of ultraviolet B radiation-induced tumor necrosis factor production by the epidermal platelet-activating factor receptor (1999) J Biol Chem, 274 (38), pp. 26917-26921; Müller, K., Meineke, V., Radiation-induced alterations in cytokine production by skin cells (2007) Exp Hematol, 35 (4 SUPPL. 1), pp. 96-104; Tolle, D.V., Seed, T.M., Fritz, T.E., Lombard, L.S., Poole, C.M., Acute monocytic leukemia in an irradiated Beagle (1979) Vet Pathol, 16 (2), pp. 243-254; Seed, T.M., Chubb, G.T., Tolle, D.V., Sequential changes in bone marrow architecture during continuous low dose gamma irradiation (1981) Scan Electron Microsc, 4, pp. 61-72; Sato, H., Seiki, M., Regulatory mechanism of 92 kDa type IV collagenase gene expression which is associated with invasiveness of tumor cells (1993) Oncogene, 8, pp. 395-405; Wielockx, B., Lannoy, K., Shapiro, S.D., Inhibition of matrix metalloproteinases blocks lethal hepatitis and apoptosis induced by tumor necrosis factor and allows safe antitumor therapy (2001) Nat Med, 7, pp. 1202-1208; Heissig B, Hattori K, Dias S, Friedrich M, Ferris B, et al. (2002) Recruitment of stem and progenitor cells from the bone marrow niche requires MMP-9 mediated release of kit-ligand. Cell 31:109(5): 625-37.35Natoli G, Costanzo A, Guido F, Moretti F, Bernardo A, et al. (1998) Nuclear factor kB-independent cytoprotective pathways originating at tumor necrosis factor receptor-associated factor 2. J Biol Chem 273(47): 31262-72.36Barkett, M., Gilmore, T.D., Control of apoptosis by Rel/NF-kappaB transcription factors (1999) Oncogene, 18 (49), pp. 6910-6924; Priestley, G.V., Scott, L.M., Ulyanova, T., Papayannopoulou, T., Lack of a4 integrin expression in stem cells restricts competitive function and self-renewal activity (2006) Blood, 107, pp. 2959-2967; Walkley, C.R., Shea, J.M., Sims, N.A., Purton, L.E., Orkin, S.H., Rb regulates interactions between hematopoietic stem cells and their bone marrow microenvironment (2007) Cell, 129 (6), pp. 1081-1095. , A; Walkley, C.R., Olsen, G.H., Dworkin, S., Fabb, S.A., Swann, J., A microenvironment-induced myeloproliferative syndrome caused by retinoic acid receptor gamma deficiency (2007) Cell, 129 (6), pp. 1097-1110. , B; Leone, G., Pagano, L., Ben-Yehuda, D., Voso, M.T., Therapy-related leukemia and myelodysplasia: Susceptibility and incidence (2007) Haematologica, 92 (10), pp. 1389-1398; Reza, S., Shetty, V., Dar, S., Qawi, H., Raza, A., Tumor necrosis factor-α levels decrease with anticytokine therapy in patients with myelodysplastic syndromes (1998) J Interferon Cytokine Res, 18 (10), pp. 871-877; Raza, A., Qawi, H., Lisak, L., Andric, T., Dar, S., Patients with myelodysplastic syndromes benefit from palliative therapy with amifostine, pentoxifylline, and ciprofloxacin with or without dexamethasone (2000) Blood, 95 (5), pp. 1580-1587
Keywords: angiogenesis; animal; animal cell; animal experiment; animal model; animal tissue; Animals; Antibodies, Neutralizing; apoptosis; article; Blood; blood cell count; Blotting, Western; bone marrow; bone marrow cell; Bone Marrow Cells; C57BL mouse; Cell Line; clinical feature; controlled study; cytokine production; disease course; drug effect; Enzyme Activation; flow cytometry; genetics; immunology; in vitro study; in vivo study; irradiation; leukocyte; leukocyte count; Leukocytes; macrocytic anemia; male; matrix metalloproteinase; Matrix Metalloproteinases; megakaryocyte; Megakaryocytes; metabolism; Mice; Mice, Inbred C57BL; Mice, Knockout; microenvironment; microsatellite marker; mouse; mouse mutant; Mus; myelodysplastic syndrome; neovascularization (pathology); Neovascularization, Pathologic; neutralizing antibody; nonhuman; Pathology; phenotype; protein expression; radiation dose; radiation exposure; Reverse Transcriptase Polymerase Chain Reaction; reverse transcription polymerase chain reaction; thrombocytopenia; transcription factor RelA; tumor necrosis factor alpha; tumor necrosis factor alpha antibody; Tumor Necrosis Factor-alpha; Vascular Endothelial Growth Factor A; vascularization; vasculotropin; vasculotropin A; Western blotting; zymography

Cationic liposome-DNA complexes as gene delivery vectors: Development and behaviour towards bone-like cells - Oliveira, A.C.; Ferraz, M.P.; Monteiro, F.J.; Simões, S. (Acta BiomaterialiaActa Biomater., 2009)
Modulation of the biological pathways responsible for fracture repair and osteogenisis may accelerate regeneration. Gene therapy is an alternative method for the release of osteogenisis-stimulating proteins into tissues. The development of vectors for gene release is still a problem in terms of ethics and techniques. In this work we evaluated whether cationic liposomes constitute a valuable strategy for the release of genetic material into bone tissue cells as non-viral vectors. Liposomes were prepared with 1,2-dioleoyl-3-trimethylammonium propane (DOTAP)-2-dioleoyl-sn-glycero-3-phosphatidylethanolamine and DOTAP-cholesterol, and characterized according to their size, zeta potential, DNA protection capacity and cytotoxicity. Transfection studies were also carried out using pCMVβ-gal plasmid in two osteoblastic cell lines (MG63 and MC3T3-E1) and in the 294T line, varying the charge ratio and the applied DNA dose. Inclusion of transferrin to increase the expression was also tested. The results suggest that there is great dependency between the transfection activity and the lipid formulation, the charge ratios of the complexes, the applied DNA dose and the cell type. There were even some differences concerning both osteoblastic lines under study. The cells of the MC3T3-E1 line present greater expression levels than the cells of the MG-63 line. The conjugation of the transferrin with the complexes contributes to the increase in transfection levels, possibly due to an increase in internalization of complexes. It is thus a good strategy for inducing the expression of specific genes in osteoblast-like cells. © 2009 Acta Materialia Inc.
Cited By (since 1996): 17Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2009.02.019PubMed ID: 19332382Language of Original Document: EnglishCorrespondence Address: Ferraz, M.P.; CEBIMED, Faculdade de Ciências da Saú, Universidade Fernando Pessoa, Rua Carlos da Maia, 296, 4200-150 Porto, Portugal; email: mpferraz@ufp.ptChemicals/CAS: 1,2 dioleoyl 3 trimethylammoniopropane, 144189-73-1; DNA, 9007-49-2; transferrin, 82030-93-1; DNA, 9007-49-2; LiposomesReferences: Luo, J., Sun, M.H., Kang, Q., Peng, Y., Jiang, W., Luu, H.H., Gene therapy for bone regeneration (2005) Curr Gene Ther, 5 (2), pp. 167-179;Oreffo, R.O.C., Triffitt, J.T., Future potentials for using osteogenic stem cells and biomaterials in orthopedics (1999) Bone, 25 (2 SUPPL. 1), pp. 5S-9S; Laurencin, C.T., Attawia, M.A., Lu, L.Q., Borden, M.D., Lu, H.H., Gorum, W.J., Poly(lactide-co-glycolide)/hydroxyapatite delivery of BMP-2-producing cells: a regional gene therapy approach to bone regeneration (2001) Biomaterials, 22 (11), pp. 1271-1277; Katz, J.L., (1996) Applications of materials in medicine and dentistry: orthopedic applications, , Academic Press, San Diego, CA p. 335-46; Bucholz, R., Nonallograft osteoconductive bone grafts substitutes (2002) Clin Orthop, 395, pp. 44-52; Kirker-Head, C.A., Potential applications and delivery strategies of bone morphogenetic proteins (2000) Adv Drug Deliv Rev, 43, pp. 65-92; Chen, Y., Luk, K.D.K., Cheung, K.M.C., Xu, R., Lin, M.C., Lu, W.W., Gene therapy for new bone formation using adeno-associated viral bone morphogenetic protein-2 vectors (2003) Gene Ther, 10 (16), pp. 1345-1353; Tseng, W.-C., Huang, L., Liposome-based gene therapy (1998) Res Focus, 1 (5); Leach, J.K., Mooney, D., Bone engineering by controlled delivery of osteoinductive molecules and cells (2004) Expert Opin, 4 (7); Dragoo, J.L., Choi, J.Y., Lieberman, J.R., Huang, J., Zuk, P.A., Zhang, J., Bone induction by BMP-2 transduced stem cells derived from human fat (2003) J Orthop Res, 21 (4), pp. 622-629; Eliyahu, H., Barenholz, Y., Domb, A.J., Polymers for DNA delivery (2005) Molecules, 10, pp. 34-64; Penque, D., Terapia génica: um objectivo ou uma realidade (2000) Boletim Biotecnol, 66, pp. 16-19; Winn, S.R., Hu, Y., Sfeir, C., Hollinger, J.O., Gene therapy approaches for modulating bone regeneration (2000) Adv Drug Deliv Rev, 42 (1-2), pp. 121-138; Lima, N., Mota, M., (2003) Biotecnologia, fundamentos e aplicações, , Lidel, Lisboa p. 368-73; Luo, D., Saltzman, W.M., Synthetic DNA delivery systems (2000) Nat Biotechnol, 18, pp. 33-37; Kikuchi, H., Suzuki, N., Ebihara, K., Morita, H., Ishii, Y., Kikuchi, A., Gene delivery using liposome technology (1999) J Control Release, 62 (1-2), pp. 269-277; Liu, F., Huang, L., Development of non-viral vectors for systemic gene delivery (2002) J Control Release, 78 (1-3), pp. 259-266; Girao da Cruz, M.T., Simoes, S., Pires, P.P.C., Nir, S., Pedroso de Lima, M.C., Kinetic analysis of the initial steps involved in lipoplex-cell interactions: effect of various factors that influence transfection activity (2001) Biochim Biophys Acta (BBA) - Biomembr, 1510 (1-2), pp. 136-151; Zuidam, N.J., Barenholz, Y., Electrostatic and structural properties of complexes involving plasmid DNA and cationic lipids commonly used for gene delivery (1998) Biochim Biophys Acta (BBA) - Biomembr, 1368 (1), pp. 115-128; Tros de Ilarduya, C., Arangoa, M.A., Moreno-Aliaga, M.J., Duzgunes, N., Enhanced gene delivery in vitro and in vivo by improved transferrin-lipoplexes (2002) Biochim Biophys Acta (BBA) - Biomembr, 1561 (2), pp. 209-221; Simoes, S., Pires, P., Cruz, M.T.G.d., Duzgunes, N., Pedroso de Lima, M.C., Gene delivery by cationic liposome-DNA complexes containing transferrin or serum albumin (2003) Methods Enzymol, 373, pp. 369-383; Woo-Jeong, C., Jin-Ki, K., Sung-Hee, C., Jeong-Sook, P., Woong Shick, A., Kima, C.-K., Low toxicity of cationic lipid-based emulsion for gene transfer (2004) Biomaterials, 25 (27), pp. 5893-5903; Koe, G.S., Way, H.L., Quentingco, G.M., Smith, J.G., Wedeking, T., Niven, R.W., The effect of mixing on the formation of DNA/liposome complexes (1997) Pharmacy, p. 14; Lasic, D.D., Templeton, N.S., Liposomes in gene therapy (1996) Adv Drug Deliv Rev, 20 (2-3), pp. 221-266; Pedroso de Lima, M.C., Simoes, S., Pires, P., Faneca, H., Duzgunes, N., Cationic lipid-DNA complexes in gene delivery: from biophysics to biological applications (2001) Adv Drug Deliv Rev, 47 (2-3), pp. 277-294; Hirsch-Lerner, D., Zhang, M., Eliyahu, H., Ferrari, M.E., Wheeler, C.J., Barenholz, Y., Effect of "helper lipid" on lipoplex electrostatics (2005) Biochim Biophys Acta (BBA) - Biomembr, 1714 (2), pp. 71-84; Torricelli, P., Fini, M., Giavaresi, G., Borsari, V., Carpi, A., Nicolini, A., Comparative interspecies investigation on osteoblast cultures: data on cell viability and synthetic activity (2003) Biomed Pharmacother, 57 (1), pp. 57-62; Corsi, K., Chellat, F., Yahia, L., Fernandes, J.C., Mesenchymal stem cells, MG63 and HEK293 transfection using chitosan-DNA nanoparticles (2003) Biomaterials, 24 (7), pp. 1255-1264; Mislick, K.A., Baldeschwieler, J.D., Evidence for role of proteoglycans in cation-mediated gene transfer (1996) Proc Natl Acad Sci USA, 93 (22), pp. 12349-12354; Duzgunes, N., Nir, S., Mechanisms and kinetics of liposome-cell interactions (1999) Adv Drug Deliv Rev, 40 (1-2), pp. 3-18; Radwan Almofti, M., Harashima, H., Shinohara, Y., Almofti, A., Baba, Y., Kiwada, H., Cationic liposome-mediated gene delivery: biophysical study and mechanism of internalization (2003) Arch Biochem Biophys, 410 (2), pp. 246-253; Simões, S., Filipe, A., Faneca, H., Mano, M., Penacho, N., Duzgunes, N., Cationic liposomes for gene delivery (2005) Expert Opin, 2 (2); Rejman, J., Bragonzi, A., Conese, M., Role of clathrin- and caveolae-mediated endocytosis in gene transfer mediated by lipo- and polyplexes (2005) Mol Ther, 12 (3), pp. 468-474
Keywords: 1,2 dioleoyl 3 trimethylammoniopropane; animal cell; Animals; article; bone cell; bone development; bone tissue; Cationic liposomes; Cell Line; cell type; complex formation; controlled study; Cytotoxicity; DNA; drug mechanism; gene expression regulation; Gene therapy; Gene transfer; genetic transfection; Genetic Vectors; human; human cell; internalization; lipoplex; liposome; Liposomes; materials testing; Mice; nonhuman; nonviral gene delivery system; osteoblast; Osteoblasts; Osteogenesis; Particle Size; plasmid; priority journal; Transfection; transferrin; Zeta potential

Chromatographic pattern recognition using optimized one-class classifiers - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2009)
This paper presents a method for automating the selection of the rejection rate of one-class classifiers aiming at optimizing the classifier performance. These classifiers are used in a new classification approach to deal with class imbalance in Thin-Layer Chromatography (TLC) patterns, which is due to the huge difference between the number of normal and pathological cases, as a consequence of the rarity of Lysosomal Storage Disorders (LSD) diseases. The classification is performed in two decision stages, both implemented using optimized one-class classifiers: the first stage aims at recognizing most of the normal samples; the outliers of this first decision level are presented to the second stage, which is a multiclassifier prepared to deal with both pathological and normal patterns. The results that were obtained proved that the proposed methodology is able to overcome some of the difficulties associated with the choice of the rejection rate of one-class classifiers, and generally contribute to the minimization of the imbalance problem in TLC pattern classification. © 2009 Springer Berlin Heidelberg.
Conference code: 77027Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-02172-5_58Language of Original Document: EnglishCorrespondence Address: Sousa, A. V.; Instituto de Engenharia Biomédica, Rua Roberto Frias, Porto 4200-465, Portugal; email: ats@isep.ipp.ptReferences: Skurichina, M., Raudys, S., Duin, R.P.W., K-Nearest Neighbors Directed Noise Injection in Multilayer Perceptron Training (2000) IEEE Transactions on Neural Networks, 11;Chawla, N.V., Japkowicz, N., Kolcz, A., Editorial: Special Issue: Learning from Imbal-anced Data Sets (2004) Sigkdd Explorations, 6, pp. 1-6; Tax, D.M.J., (2001) One-class Classification; Concept-learning in the Absence of Counterexamples, , Ph.D. thesis: Delft University of Technology; Durand, G., Seta, N., Protein Glycosylation and Diseases: Blood and Urinary Oligosac-charides as Markers for Diagnosis and Therapeutic Monitoring (2000) Clin. Chem, 46, pp. 795-805; Sewell, A.C., Urinary Oligosaccharides. Techniques in Diagnostic Human (1991) Biochemical Genetics, pp. 219-231; Pekalska, E., Duin, R.P.W., Dissimilarity Representations Allow for Building Good Classifiers (2002) Pattern Recogn. Lett, 23, pp. 943-956; Sousa, A.V., Mendonça, A.M., Campilho, A., Dissimilarity-based Classification of Chromatographic Profiles (2008) Pattern Analysis and Applications, 11 (3-4), pp. 409-423; Sousa, A.V., Mendonça, A.M., Campilho, A., Minimizing the Imbalance Problem in Chromatographic Profile Classification with One-class Classifiers (2008) LNCS, 5112, pp. 413-422. , Campilho, A, Kamel, M.S, eds, ICIAR 2008, Springer, Heidelberg; Sousa, A.V., Mendonça, A.M., Campilho, A., Chromatographic Pattern Classification (2008) IEEE Trans. on Biomedical Engineering, 55 (6), pp. 1687-1696; Visa, S., Ralescu, A., Learning Imbalanced and Overlapping Classes Using Fuzzy Sets (2003) Workshop on Learning from Imbalanced Datasets II, ICML, , Washington DC Sponsors: International Association for Pattern Recognition (IAPR); Fundacao para a Ciencia e a Tecnologia (FCT)
Keywords: Chromatographic analysis; Class imbalance; Classification approach; Classifier performance; Classifiers; Decision levels; Image analysis; Imbalance problem; Learning systems; Lysosomal storage disorder; Multi-classifier; One-class classifier; Optimization; Pathological case; Pattern classification; Pattern recognition; Rejection rates; Thin layer chromatography

Corrected and improved model for educational simulation of neonatal cardiovascular pathophysiology - Zijlmans, M.; Sá-Couto, C.D.; van Meurs, W.L.; Goodwin, J.A.; Andriessen, P. (Simulation in HealthcareSimul. Healthc., 2009)
We identified errors in the software implementation of the mathematical model presented in: Sá Couto CD, van Meurs WL, Goodwin JA, Andriessen P. A model for educational simulation of neonatal cardiovascular pathophysiology. Simul Healthcare 2006;1:4-12. Simulation results obtained with corrected code are presented for future reference. All but one of the simulation results do not differ by more than 9% from the previously published results. The heart rate response to acute loss of 30% of blood volume, simulated with corrected code is stronger than published target data. This modeling error was masked by errors in code implementation. We improved this response and the model by adjusting the gains and adding thresholds and saturations in the baroreflex model. General considerations on identification of model and code errors and model validity are presented. Copyright © 2009 Society for Simulation in Healthcare.
Cited By (since 1996): 4Export Date: 21 November 2012Source: Scopusdoi: 10.1097/SIH.0b013e31818b27a8Language of Original Document: EnglishCorrespondence Address: Zijlmans, M.; INEB-Instituto de Engenharia Biomédica, Porto, PortugalReferences: Sá Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Andriessen, P., A model for educational simulation of neonatal cardiovascular pathophysiology (2006) Simul Healthc, 1, pp. 4-12;Goodwin, J.A., Van Meurs, W.L., Sá Couto, C.D., Beneken, J.E.W., Graves, S.A., A model for educational simulation of infant cardiovascular physiology (2004) Anesth Analg, 99, pp. 1655-1664; Beneken, J.E.W., A mathematical approach to cardiovascular function (1965) The Uncontrolled Human System, , Thesis, University of Utrecht, The Netherlands; Andriessen, P., Bambang Oetomo, S., Peters, C., Vermeulen, B., Wijn, P.F.F., Blanco, C.E., Baroreceptor reflex sensitivity in human neonates: The effect of postmenstrual age (2005) J Physiol, 568, pp. 333-341; Segar, J.L., Roghair, R.D., Segar, E.M., Bailey, M.C., Scholz, T.D., Lamb, F.S., Early gestation dexamethasone alters baroreflex and vascular responses in newborn lambs before hypertension (2006) Am J Physiol Regul Integr Comp Physiol, 291, pp. R481-R488; Wallgren, G., Barr, M., Rudhe, U., Hemodynamic studies of induced acute hypo- and hypervolemia in the newborn infant (1964) Acta Paediatr, 53, pp. 1-12
Keywords: aorta coarctation; article; Baroreflex; bleeding; blood pressure; blood volume; Cardiac Output; cardiovascular disease; Cardiovascular Diseases; Cardiovascular physiology; computer program; Computer simulation; Congenital heart defect; congenital heart malformation; diastolic blood pressure; Education, Medical; Erratum; Fallot tetralogy; great vessels transposition; heart output; Heart rate; heart right ventricle pressure; human; Humans; Infant, Newborn; lung pressure; mathematical model; mean arterial pressure; medical education; medical error; methodology; Neonate; Neonatology; newborn; patent ductus arteriosus; pathophysiology; physiology; pressoreceptor reflex; priority journal; simulation; Software Design; systolic blood pressure; Validation; validity; vascular resistance; Verification; vital sign

Cytotoxicity evaluation of nanocrystalline diamond coatings by fibroblast cell cultures - Amaral, M.; Gomes, P.S.; Lopes, M.A.; Santos, J.D.; Silva, R.F.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2009)
The cytotoxicity profile of nanocrystalline diamond (NCD) coatings on a Si 3N 4 ceramic was investigated. This material is envisaged to have biomedical dental applications such as burrs and surgical instruments. Two fibroblast cell culture systems were used to address the cytotoxicity of NCD-coated samples: L929 cells (a mouse permanent cell line) and human gingival fibroblasts. Cell behavior was evaluated in terms of cell adhesion, cell viability/proliferation (mitochondrial function, MTT assay) and the pattern of cell growth. Fibroblast cell behavior on standard polystyrene culture plates was used as control, as Si 3N 4 substrates have previously been shown to be biocompatible. NCD coatings provided a suitable surface for cell attachment, spreading and proliferation. Human gingival cells showed a homogeneous cytoplasm spreading, a flattened elongated morphology and a typical parallel alignment on confluent cultures. In comparison, L929 cells denoted a lower cytoplasm expansion, a heterogeneous spreading but a higher proliferation rate. For both cells, after few days, the NCD coating was completely covered with continuous cell layers. As compared to standard polystyrene culture plates, no deleterious or cytotoxic responses were observed with L929 and human fibroblast cell cultures, and in both a slight enhancement in cell proliferation was observed. In addition, the seeded NCD film allowed reproduction of the typical features of the two cell culture systems tested, further suggesting the lack of cytotoxicity of this coating. © 2008 Acta Materialia Inc.
Cited By (since 1996): 8Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2008.08.015PubMed ID: 18819854Language of Original Document: EnglishCorrespondence Address: Amaral, M.; CICECO, Department of Ceramics and Glass Engineering, University of Aveiro, 3810-193 Aveiro, Portugal; email: margarida.amaral@ua.ptChemicals/CAS: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide, 298-93-1; diamond, 7782-40-3; polystyrene, 9003-53-6; silicon nitride, 12033-89-5; Culture Media; Diamond, 7782-40-3References: Griffin, J., Ray, P.C., Role of inert gas in the low-temperature nano-diamond chemical vapour deposition process (2006) Nanotechnology, 17, pp. 1225-1229;Mitura, S., Mitura, K., Niedzielski, P., Louda, P., Danilenko, V., Nanocrystalline diamond, its synthesis, properties and applications (2006) J Achievements Mater Manuf Eng, 16, pp. 9-16; Okrój, W., Kamińska, M., Klimek, L., Szymański, W., Walkowiak, B., Blood platelets in contact with nanocrystalline diamond surfaces (2006) Diamond Relat Mater, 15, pp. 1535-1539; Xiao, X., Wang, J., Liu, C., Carlisle, J.A., Mech, B., Greenberg, R., In vitro and in vivo evaluation of ultrananocrystalline diamond for coating of implantable retinal microchips (2006) J Biomed Mater Res B: Appl Biomater, 77 B, pp. 273-281; Tang, L., Tsai, C., Gerberich, W.W., Kruckeberg, L., Kania, D.R., Biocompatibility of chemical-vapour-deposited diamond (1995) Biomaterials, 16, pp. 483-488; Steinmueller-Nethl, D., Kloss, F.R., Haq, M.N.U., Rainer, M., Larsson, K., Linsmeier, C., Strong binding of bioactive BMP-2 to nanocrystalline diamond by physisorption (2006) Biomaterials, 27, pp. 4547-4556; Wenmackers, S., Christiaens, P., Daenen, M., Haenen, K., Nesládek, M., Ven, M., DNA attachment to nanocrystalline diamond films (2005) Phys Status Solidi, 202, pp. 2212-2216; Retama, J.R., Hernando, J., Lopez-Ruiz, B., Härtl, A., Steinmüller, D., Stutzmann, M., Synthetic nanocrystalline diamond as a third-generation biosensor support (2006) Langmuir, 22, pp. 5837-5842; Siew, P.S., Loh, K.P., Poh, W.C., Zhang, H., Biosensing properties of nanocrystalline diamond film grown on polycrystalline diamond electrodes (2005) Diamond Relat Mater, 14, pp. 426-431; Jakubowski, W., Bartosz, G., Niedzielski, P., Szymanski, W., Walkowiak, B., Nanocrystalline diamond surface is resistant to bacterial colonization (2004) Diamond Relat Mater, 13, pp. 1761-1763; Trava-Airoldi, V.J., Corat, E.J., Leite, N.F., Nono, M., Ferreira, N.G., Baranauskas, V., CVD diamond burrs-development and applications (1996) Diamond Relat Mater, 5, pp. 857-860; Amar, M., Ahmed, W., Sein, H., Jones, A.N., Rego, C., Chemical vapour deposition of diamond coatings onto molybdenum dental tools (2003) J Phys Condens Matter, 15, pp. S2977-S2982; Tetsumura, A., Honda, E., Sasaki, T., Kino, K., Metallic residues as a source of artifacts in magnetic resonance imaging of the temporomandibular joint (1999) Dentomaxillofac Radiol, 28, pp. 186-190; Carvalho, C.A., Fagundes, T.C., Barata, T.E., Trava-Airoldi, V.J., Navarro, M.L., The use of CVD diamond burrs for ultraconservative cavity preparations: a report of two cases (2007) J Esthet Restor Dent, 19, pp. 19-29; Mitura, K., Niedzielski, P., Grzegorz, B., Moll, J., Walkowiak, B., Pawlowska, Z., Interactions between carbon coatings and tissue (2006) Surf Coat Technol, 201, pp. 2117-2123; Fries, M.D., Vohra, Y.K., Microcrystalline and nanocrystalline diamond film deposition on cobalt chrome alloy (1999) Thin films-stresses and mechanical properties VIII, , Vinci R., Kraft O., Moody N., Besser P., and Shaffer II E. (Eds), MRS Publications, Boston, MA; Fries, M.D., Vohra, Y.K., Properties of nanocrystalline thin films grown by MPCVD for biomedical implant purposes (2004) Diamond Relat Mater, 13, pp. 1740-1743; Papo, M.J., Catledge, S.A., Vohra, Y.K., Mechanical wear behavior of nanocrystalline and multilayer diamond coatings on temporomandibular joint implants (2004) J Mater Sci: Mater Med, 15, pp. 773-777; Sun, F.H., Zhang, Z.M., Ma, Y.P., Chen, M., Synthesis of nanocrystalline diamond films on smooth WC-Co cemented carbide substrates (2007) Int J Abrasive Technol, 1, pp. 161-172; Belmonte, M., Fernandes, A.J.S., Costa, F.M., Oliveira, F.J., Silva, R.F., Adhesion behaviour assessment on diamond coated silicon nitride by acoustic emission (2003) Diamond Relat Mater, 12, pp. 733-737; Petzow, G., Herrmann, M., Silicon nitride ceramics (2002) Struct Bond, 102, pp. 47-167; Amaral, M., Costa, M.A., Lopes, M.A., Silva, R.F., Santos, J.D., Fernandes, M.H., Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and osteogenic differentiation of human bone marrow cells (2002) Biomaterials, 23, pp. 4897-4906; Kue, R., Sahrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201; Popov, C., Kulisch, W., Jelinek, M., Bock, A., Strnad, J., Nanocrystalline diamond/amorphous carbon composite films for applications in tribology, optics and biomedicine (2006) Thin Solid Films, 494, pp. 92-97; Chong, K.F., Loh, K.P., Vedula, S.R., Lim, C.T., Sternschulte, H., Steinmüller, D., Cell adhesion properties on photochemically functionalized diamond (2007) Langmuir, 23, pp. 5615-5621; Bajaj, P., Akin, D., Gupta, A., Sherman, D., Shi, B., Auciello, O., Ultra-nanocrystalline diamond film as an optimal cell interface for biomedical applications (2007) Biomed Microdevices, , [Epub ahead of print]; Arnold, L.F., Baram, B., In vitro culture of periodontal ligament cells (1972) J Dent Res, 51, pp. 953-959; Piche, J.E., Carnes Jr., D.L., Graves, D.T., Initial characterization of cells derived from human periodontia (1989) J Dent Res, 68, pp. 761-767; Trigo Cabral, C., Costa, M.A., Fernandes, M.H., In vitro models of periodontal cells: a comparative study of long-term gingival, periodontal ligament and alveolar bone cell cultures in the presence of β-glycerophosphate and dexamethasone (2007) J Mater Sci: Mater Med, 18, pp. 1079-1088; Bajpai, P.K., Billote, W.G., Ceramic biomaterials (1995) The biomedical engineering handbook, pp. 552-580. , Bronzino J.D. (Ed), CRC Press, Boca Raton, FL; Nishitani-Gamo, M., Ando, T., Watanabe, K., Sekita, M., Dennig, P.A., Yamamoto, K., Interfacial structures of oriented diamond on Si (1 0 0) characterized by confocal Raman spectroscopy (1997) Diamond Relat Mater, 6, pp. 1036-1040; Ferrari, A.C., Robertson, J., Origin of the 1150 cm -1 Raman mode in nanocrystalline diamond (2001) Phys Rev B, 63, pp. 121405-1-121405-4; Pfeiffer, R., Kuzmany, H., Knoll, P., Bokova, S., Salk, N., Günther, B., Evidence for trans-polyacetylene in nano-crystalline diamond films (2003) Diamond Relat Mater, 12, pp. 268-271; Zimmermann, T., Janischowsky, K., Denisenko, A., Guillén, F.J.H., Kubovic, M., Gruen, D.M., Nanocrystalline diamond pn-structure grown by hot-filament CVD (2006) Diamond Relat Mater, 15, pp. 203-206; Krauss, A.R., Auciello, O., Gruen, D.M., Jayatissa, A., Sumant, A., Tucek, J., Ultrananocrystalline diamond thin films for MEMS and moving mechanical assembly devices (2001) Diamond Relat Mater, 10, pp. 1952-1961; Amaral, M., Fernandes, A.J.S., Vila, M., Oliveira, F.J., Silva, R.F., Growth rate improvements in the hot-filament CVD deposition of nanocrystalline diamond (2006) Diamond Relat Mater, 15, pp. 1822-1827; Alberts, B., Johnson, A., Lewis, J., Raff, M., Roberts, K., Walter, P., The cytoskeleton (2002) Molecular biology of the cell. 4th ed., pp. 907-972. , Alberts B., Johnson A., Lewis J., Raff M., Roberts K., and Walter P. (Eds), Garland Publishing, New York; Stamenovic, D., Effects of cytoskeletal prestress on cell rheological behaviour (2005) Acta Biomater, 1, pp. 255-262; Freshney, T.I., Biology of cultured cells (2000) Culture of animal cells. A manual of basic technique, pp. 9-18. , Wiley-Liss, New York; Garguilo, J.M., Davis, B.A., Buddie, M., Köck, F.A.M., Nemanich, R.J., Fibrinogen adsorption onto microwave plasma chemical vapor deposited diamond films (2004) Diamond Relat Mater, 13, pp. 595-599; Ariano, P., Baldellia, P., Carbonea, E., Gilardino, A., Giudicea, A.L., Lovisolo, D., Cellular adhesion and neuronal excitability on functionalised diamond surfaces (2005) Diamond Relat Mater, 14, pp. 669-674; Heinrich, G., Grijgler, T., Rosiwal, S.M., Singer, R.F., CVD diamond coated titanium alloys for biomedical and aerospace applications (1997) Surf Coat Technol, 94-95, pp. 514-520; Müller, R., Adamschik, M., Steidl, D., Kohn, E., Thamasett, S., Stiller, S., Application of CVD-diamond for catheter ablation in the heart (2004) Diamond Relat Mater, 13, pp. 1080-1083; Nordsletten, L., Hogasen, A.K.M., Konttinen, Y.T., Santavirta, S., Aspenberg, P., Aasen, A.O., Human monocytes stimulation by particles of hydroxyapatite, silicon carbide and diamond: in vitro studies of new prosthesis coatings (1996) Biomaterials, 17, pp. 1521-1527; Aspenberg, P., Antilla, A., Konttinen, Y.T., Lappalainen, R., Goodman, S.B., Nordsletten, L., Benign response to particles of diamond and SiC: bone chamber studies of new joint replacement coating materials in rabbits (1996) Biomaterials, 17, pp. 807-812; Specht, C.G., Williams, O.A., Jackman, R.B., Schoepfer, R., Ordered growth of neurons on diamond (2004) Biomaterials, 25, pp. 4073-4078; Schrand, A.M., Huang, H., Carlson, C., Schlager, J.J., Omacr Sawa, E., Hussain, S.M., Are diamond nanoparticles cytotoxic? (2007) J Phys Chem B, 111, pp. 2-7; International Organization for Standardization, ISO 10993-5: biological evaluation of medical devices. Part 5. Tests for cytotoxicity: in vitro methods. Geneva; 1992International Organization for Standardization, ISO 7405: dentistry-preclinical evaluation of biocompatibility of medical devices used in dentistry-test methods for dental materials. Geneva; 1997Kaplan, F.S., Hayes, W.C., Keaveny, T.M., Boskey, A., Einhorn, T.A., Iannotti, J.P., Form and function of bone (1994) Orthopedic basic science, pp. 127-185. , Simon S.P. (Ed), American Academy of Orthopedic Surgeons, Columbus, OH; Webster, T.J., Proteins: structure and interactions patterns to solid surfaces (2004) Encyclopedia of nanoscience and nanotechnology, pp. 3079-3095. , Schwarz J.A., Contescu C., and Putyera K. (Eds), Marcel Dekker, New York; Webster, T.J., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21, pp. 1803-1810; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Specific proteins mediate enhanced osteoblast adhesion on nanophase ceramics (2000) J Biomed Mater Res, 51, pp. 475-483; Shane, A.C., Marc, D.F., Yogesh, K.V., William, R.L., Jack, E.L., Shanna, W., Nanostructured ceramics for biomedical implants (2002) J Nanosci Nanotechnol, 2, pp. 1-20; Price, R.L., Haberstroh, K.M., Webster, T.J., Enhanced functions of osteoblasts on nanostructured surfaces of carbon and alumina (2003) Med Biol Eng Comput, 41, pp. 372-375; Webster, T.J., Siegel, R.W., Bizios, R., Osteoblast adhesion on nanophase ceramics (1999) Biomaterials, 20, pp. 1221-1227; Perla, V., Webster, T.J., Better osteoblast adhesion on nanoparticulate selenium-A promising orthopedic implant material (2005) J Biomed Mater Res, 75 A, pp. 356-364
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; animal cell; Animals; article; Biocompatibility; Biomedical dental applications; biomedicine; cell adhesion; Cell Division; cell function; cell growth; Cell Line; cell proliferation; cell spreading; cell structure; cell surface; cell survival; cell viability; ceramics; controlled study; Culture Media; cytoplasm; Cytotoxicity; dentistry; diamond; Fibroblast cell cultures; fibroblast culture; Fibroblasts; gingiva; human; human cell; Humans; material coating; Mice; Microscopy, Electron, Scanning; mitochondrial respiration; mouse; nanocrystal; Nanocrystalline diamond coating; Nanostructures; nonhuman; polystyrene; priority journal; Silicon nitride; Surgical instrument

Decision trees using the minimum Entropy-of-error principle - De Sá, J.P.M.; Gama, J.; Sebastião, R.; Alexandre, L.A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2009)
Binary decision trees based on univariate splits have traditionally employed so-called impurity functions as a means of searching for the best node splits. Such functions use estimates of the class distributions. In the present paper we introduce a new concept to binary tree design: instead of working with the class distributions of the data we work directly with the distribution of the errors originated by the node splits. Concretely, we search for the best splits using a minimum entropy-of-error (MEE) strategy. This strategy has recently been applied in other areas (e.g. regression, clustering, blind source separation, neural network training) with success. We show that MEE trees are capable of producing good results with often simpler trees, have interesting generalization properties and in the many experiments we have performed they could be used without pruning. © 2009 Springer Berlin Heidelberg.
Conference code: 77256Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-03767-2_97Language of Original Document: EnglishCorrespondence Address: De Sá, J. P. M.; INEB-Instituto de Engenharia Biomédica, Porto, Portugal; email: jmsa@fe.up.ptReferences: Asuncion, A., Newman, D.J., (2007) UCI Machine Learning Repository, , http://www.ics.uci.edu/̃mlearn/MLRepository.html, Univ. of California, SICS, Irvine, CA;Breiman, L., Friedman, J.H., Olshen, R.A., Stone, C.J., (1993) Classification and Regression Trees, , Chapman & Hall/CRC, Boca Raton; Devroye, L., Giörfi, L., Lugosi, G., (1996) A Probabilistic Theory of Pattern Recognition, , Springer, Heidelberg; Forina, M., Armanino, C., Eigenvector Projection and Simplified Nonlinear Mapping of Fatty Acid Content of Italian Olive Oils (1981) Ann. Chim, 72, pp. 127-155; Loh, W.-Y., Shih, Y.-S., Split Selection Methods for Classification Trees (1997) Statistica Sinica, 7, pp. 815-840; Marques de Sá, J.P., (2007) Applied Statistics Using SPSS, STATISTICA, MATLAB and R, , 2nd edn. Springer, Heidelberg; Quinlan, J.R., Induction of Decision Trees (1986) Machine Learning, 1, pp. 81-106; Quinlan, J.R.: C4.5 Programs for Machine Learning. Morgan Kaufmann, San Francisco (1993)Silva, L.M., Felgueiras, C.S., Alexandre, L.A., Marques de Sá, J., Error Entropy in Classification Problems: A Univariate Data Analysis (2006) Neural Comp, 18, pp. 2036-2061; Silva, L.M., Embrechts, M.J., Santos, J.M., de Sá, J.M., The influence of the risk functional in data classification with mLPs (2008) LNCS, 5163, pp. 185-194. , Kůrková, V, Neruda, R, Koutník, J, eds, ICANN 2008, Part I, Springer, Heidelberg Sponsors: University of Munster; International Association for Pattern Recognition; Olympus Soft Imaging Solutions GmbH; Philips
Keywords: Binary decision trees; Binary trees; Blind source separation; Class distributions; decision trees; Electronic medical equipment; entropy; entropy-of-error; Generalization properties; Image analysis; Minimum entropy; Neural network training; Neural networks; New concept; node split criteria; Univariate

Fibronectin-mediated endothelialisation of chitosan porous matrices - Amaral, I.F.; Unger, R.E.; Fuchs, S.; Mendonça, A.M.; Sousa, S.R.; Barbosa, M.A.; Pêgo, A.P.; Kirkpatrick, C.J. (BiomaterialsBiomaterials, 2009)
Chitosan (Ch) porous matrices were investigated regarding their ability to be colonized by human microvascular endothelial cells (HPMEC-ST1.6R cell line) and macrovascular endothelial cells namely HUVECs. Specifically we assessed if previous incubation of Ch in a fibronectin (FN) solution was effective in promoting endothelial cell (EC) adhesion to Ch matrices with different degrees of acetylation (DAs). Upon FN physiadsorption, marked differences were found between the two DAs investigated, namely DA 4% and 15%. While cell adhesion was impaired on Ch with DA 15%, ECs were able to not only adhere to Ch with DA 4%, but also to spread and colonize the scaffolds, with retention of the EC phenotype and angiogenic potential. To explain the observed differences between the two DAs, protein adsorption studies using 125I-FN and immunofluorescent labelling of FN cell-binding domains were carried out. In agreement with the higher cell numbers found, scaffolds with DA 4% revealed a higher number of exposed FN cell-binding domains as well as greater ability to adsorb FN and to retain and exchange adsorbed FN in the presence of competitive proteins. These findings suggest that the DA is a key parameter modulating EC adhesion to FN-coated Ch by influencing the adsorbed protein layer. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2009.06.056PubMed ID: 19615736Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; fibronectin, 86088-83-7; Biocompatible Materials; Chitosan, 9012-76-4; FibronectinsReferences: Moon, J.J., West, J.L., Vascularization of engineered tissues: approaches to promote angiogenesis in biomaterials (2008) Current Topics in Medicinal Chemistry, 8 (4), pp. 300-310;Blitterswijk, C.A., Moroni, L., Rouwkema, J., Siddappa, R., Sohier, J., Tissue engineering - an introduction (2008) Tissue engineering, , Blitterswijk C.A. (Ed), Elsevier; Ehrbar, M., Zeisberger, S.M., Raeber, G.P., Hubbell, J.A., Schnell, C., Zisch, A.H., The role of actively released fibrin-conjugated VEGF for VEGF receptor 2 gene activation and the enhancement of angiogenesis (2008) Biomaterials, 29 (11), pp. 1720-1729; Elbjeirami, W.M., West, J.L., Angiogenesis-like activity of endothelial cells co-cultured with VEGF-producing smooth muscle cells (2006) Tissue Engineering, 12 (2), pp. 381-390; Unger, R.E., Peters, K., Wolf, M., Motta, A., Migliaresi, C., Kirkpatrick, C.J., Endothelialization of a non-woven silk fibroin net for use in tissue engineering: growth and gene regulation of hunian endothelial cells (2004) Biomaterials, 25 (21), pp. 5137-5146; Fuchs, S., Motta, A., Migliaresi, C., Kirkpatrick, C.J., Outgrowth endothelial cells isolated and expanded from human peripheral blood progenitor cells as a potential source of autologous cells for endothelialization of silk fibroin biomaterials (2006) Biomaterials, 27 (31), pp. 5399-5408; Kirkpatrick, C.J., Unger, R.E., Krump-Konvalinkova, V., Peters, K., Schmidt, H., Kamp, G., Experimental approaches to study vascularization in tissue engineering and biomaterial applications (2003) Journal of Materials Science, 14 (8), pp. 677-681; Calonder, C., Matthew, H.W.T., Van Tassel, P.R., Adsorbed layers of oriented fibronectin: a strategy to control cell-surface interactions (2005) Journal of Biomedical Materials Research Part A, 75 A (2), pp. 316-323; Kouvroukoglou, S., Dee, K.C., Bizios, R., McIntire, L.V., Zygourakis, K., Endothelial cell migration on surfaces modified with immobilized adhesive peptides (2000) Biomaterials, 21 (17), pp. 1725-1733; Burdick, J.A., Khademhosseini, A., Langer, R., Fabrication of gradient hydrogels using a microfluidics/photopolymerization process (2004) Langmuir, 20 (13), pp. 5153-5156; Garcia, A.J., Get a grip: integrins in cell-biomaterial interactions (2005) Biomaterials, 26, pp. 7525-7529; Tomihata, K., Ikada, Y., In vitro and in vivo degradation of films of chitin and its deacetylated derivatives (1997) Biomaterials, 18 (7), pp. 567-575; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., Rat bone marrow stromal cells osteogenic differentiation and fibronectin adsorption on chitosan membranes: the effect of the degree of acetylation (2005) Journal of Biomedical Materials Research Part A, 75 A (2), pp. 387-397; Nettles, D.L., Elder, S.H., Gilbert, J.A., Potential use of chitosan as a cell scaffold material for cartilage tissue engineering (2002) Tissue Engineering, 8 (6), pp. 1009-1016; Oliveira, S.M., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., Engineering endochondral bone: in vitro studies (2009) Tissue Engineering, 15 (3), pp. 625-634; Freier, T., Koh, H.S., Kazazian, K., Shoichet, M.S., Controlling cell adhesion and degradation of chitosan films by N-acetylation (2005) Biomaterials, 26 (29), pp. 5872-5878; Wang, X.H., Cui, F.Z., Feng, Q.L., Li, J.C., Zhang, Y.H., Preparation and characterization of collagen/chitosan matrices as potential biomaterials (2003) Journal of Bioactive and Compatible Polymers, 18 (6), pp. 453-467; Chupa, J.M., Foster, A.M., Sumner, S.R., Madihally, S.V., Matthew, H.W.T., Vascular cell responses to polysaccharide materials: in vitro and in vivo evaluations (2000) Biomaterials, 21 (22), pp. 2315-2322; Chung, T.W., Lu, Y.F., Wang, S.S., Lin, Y.S., Chu, S.H., Growth of human endothelial cells on photochemically grafted Gly-Arg-Gly-Asp (GRGD) chitosans (2002) Biomaterials, 23 (24), pp. 4803-4809; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., Adhesive protein interactions with chitosan: consequences for valve endothelial cell growth on tissue-engineering materials (2003) Journal of Biomedical Materials Research Part A, 67 A (2), pp. 538-547; Huang, Y., Onyeri, S., Siewe, M., Moshfeghian, A., Madihally, S.V., In vitro characterization of chitosan-gelatin scaffolds for tissue engineering (2005) Biomaterials, 26 (36), pp. 7616-7627; Huang, Y., Siewe, M., Madilhally, S.V., Effect of spatial architecture on cellular colonization (2006) Biotechnology and Bioengineering, 93 (1), pp. 64-75; Kirsebom, H., Aguilar, M.R., Roman, J.S., Fernandez, M., Prieto, M.A., Bondar, B., Macroporous scaffolds based on chitosan and bioactive molecules (2007) Journal of Bioactive and Compatible Polymers, 22 (6), pp. 621-636; Cao, W.L., Jing, D.H., Li, J.M., Gong, Y.D., Zhao, N.M., Zhang, X.F., Effects of the degree of deacetylation on the physicochemical properties and Schwann cell affinity of chitosan films (2005) Journal of Biomaterials Applications, 20 (2), pp. 157-177; Amaral, I.F., Sampaio, P., Barbosa, M.A., Three-dimensional culture of human osteoblastic cells in chitosan sponges: the effect of the degree of acetylation (2006) Journal of Biomedical Materials Research Part A, 76 A (2), pp. 335-346; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42 (8), pp. 3569-3580; Vachoud, L., Zydowicz, N., Domard, A., Formation and characterisation of a physical chitin gel (1997) Carbohydrate Research, 302 (3-4), pp. 169-177; Montembault, A., Viton, C., Domard, A., Physico-chemical studies of the gelation of chitosan in a hydroalcoholic medium (2005) Biomaterials, 26 (8), pp. 933-943; Amaral, I.F., Cordeiro, A.L., Sampaio, P., Barbosa, M.A., Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation (2007) Journal of Biomaterials Science Polymer Edition, 18 (4), pp. 469-485; Krump-Konvalinkova, V., Bittinger, F., Unger, R.E., Peters, K., Lehr, H.A., Kirkpatrick, C.J., Generation of human pulmonary microvascular endothelial cell lines (2001) Laboratory Investigation, 81 (12), pp. 1717-1727; Unger, R.E., Krump-Konvalinkova, V., Peters, K., Kirkpatrick, C.J., In vitro expression of the endothelial phenotype: comparative study of primary isolated cells and cell lines, including the novel cell line HPMEC-ST1.6R (2002) Microvascular Research, 64 (3), pp. 384-397; Jaffe, E.A., Nachman, R.L., Becker, C.G., Minick, C.R., Culture of human endothelial cells derived from umbilical veins. Identification by morphologic and immunologic criteria (1973) J Clin Invest, 52 (11), pp. 2745-2756; O'Brien, J., Wilson, I., Orton, T., Pognan, F., Investigation of the Alamar blue (resazurin) fluorescent dye for the assessment of mammalian cell cytotoxicity (2000) European Journal of Biochemistry, 267 (17), pp. 5421-5426; Teixeira, C.C., Hatori, M., Leboy, P.S., Pacifici, M., Shapiro, I.M., A rapid and ultrasensitive method for measurement of DNA, calcium and protein-content, and alkaline-phosphatase activity of chondrocyte cultures (1995) Calcified Tissue International, 56 (3), pp. 252-256; Barbosa, J.N., Amaral, I.F., Águas, A.P., Barbosa, M.A., Evaluation of the effect of the degree of acetylation on the inflammatory response to 3D porous chitosan scaffolds Journal of Biomedical Materials Research Part A, , in press, doi:10.1002/jbm.a.32499; Marshall, A.J., Barker, T., Sage, E.H., Hauch, K.D., Ratner, B.D., (2004) Pore size controls angiogenesis in subcutaneously implanted porous matrices. 7th World Biomaterials Congress; 2004, , Australian Society for Biomaterials Inc., Sydney, Australia p. 710; Unger, R.E., Sartoris, A., Peters, K., Motta, A., Migliaresi, C., Kunkel, M., Tissue-like self-assembly in cocultures of endothelial cells and osteoblasts and the formation of microcapillary-like structures on three-dimensional porous biomaterials (2007) Biomaterials, 28 (27), pp. 3965-3976; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalized, self-assembled monolayers of alkanethiolates on gold (1997) Langmuir, 13 (13), pp. 3404-3413; Wendt, D., Marsano, A., Jakob, M., Heberer, M., Martin, I., Oscillating perfusion of cell suspensions through three-dimensional scaffolds enhances cell seeding efficiency and uniformity (2003) Biotechnology and Bioengineering, 84 (2), pp. 205-214; Santos, M.I., Fuchs, S., Gomes, M.E., Unger, R.E., Reis, R.L., Kirkpatrick, C.J., Response of micro- and macrovascular endothelial cells to starch-based fiber meshes for bone tissue engineering (2007) Biomaterials, 28 (2), pp. 240-248; Vestweber, D., Molecular mechanisms that control endothelial cell contacts (2000) Journal of Pathology, 190 (3), pp. 281-291; Mori, T., Irie, Y., Nishimura, S., Tokura, S., Matsuura, M., Okumura, M., Endothelial cell responses to chitin and its derivatives (1998) Journal of Biomedical Materials Research, 43 (4), pp. 469-472; Panetti, T.S., Hannah, D.F., Avraamides, C., Gaughan, J.P., Marcinkiewicz, Z., Huttenlocher, A., Extracellular matrix molecules regulate endothelial cell migration stimulated by lysophosphatidic acid (2004) Journal of Thrombosis and Haemostasis, 2 (9), pp. 1645-1656; Garcia, A.J., Boettiger, D., Integrin-fibronectin interactions at the cell-material interface: initial integrin binding and signaling (1999) Biomaterials, 20 (23-24), pp. 2427-2433; Danen, E.H.J., Sonnenberg, A., Integrins in regulation of tissue development and function (2003) Journal of Pathology, 200 (4), pp. 471-480; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) Journal of Biomedical Materials Research Part A, 66 A (2), pp. 247-259; Renner, L., Jorgensen, B., Markowski, M., Salchert, K., Werner, C., Pompe, T., Control of fibronectin displacement on polymer substrates to influence endothelial cell behaviour (2004) Journal of Materials Science-Materials in Medicine, 15 (4), pp. 387-390; Garcia, A.J., Vega, M.D., Boettiger, D., Modulation of cell proliferation and differentiation through substrate-dependent changes in fibronectin conformation (1999) Molecular Biology of the Cell, 10 (3), pp. 785-798; Koenig, A.L., Gambillara, V., Grainger, D.W., Correlating fibronectin adsorption with endothelial cell adhesion and signaling on polymer substrates (2003) Journal of Biomedical Materials Research Part A, 64 A (1), pp. 20-37; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates focal adhesion composition and signaling through changes in integrin binding (2004) Biomaterials, 25, pp. 5947-5954; Pompe, T., Kobe, F., Salchert, K., Jorgensen, B., Oswald, J., Werner, C., Fibronectin anchorage to polymer substrates controls the initial phase of endothelial cell adhesion (2003) Journal of Biomedical Materials Research Part A, 67 A (2), pp. 647-657
Keywords: Acetylation; Adhesion; Adsorption; angiogenesis; article; Biocompatible Materials; Blood vessel prostheses; cell adhesion; Cell culture; cell invasion; Cell Line; Cell lines; Cell membranes; Cell number; cell proliferation; Cell size; cell spreading; cell survival; Cell-binding domain; Chitin; Chitin/chitosan; chitosan; colony formation; controlled study; Degrees of acetylation; Electric conductivity measurement; Electric currents; Endothelial cell; Endothelial Cells; Endothelialisation; endothelium; endothelium cell; epithelization; Fibronectin; Fibronectins; human; human cell; Human microvascular endothelial cells; Humans; immunofluorescence test; Key parameters; Labels; materials testing; Matrix algebra; Neovascularization, Physiologic; phenotype; porosity; Porous matrixs; priority journal; Protein adsorption; Protein layers; Scaffold; Scaffolds; Self assembly; Tissue engineering; tissue scaffold; umbilical vein

Improving chitosan-mediated gene transfer by the introduction of intracellular buffering moieties into the chitosan backbone - Moreira, C.; Oliveira, H.; Pires, L.R.; Simões, S.; Barbosa, M.A.; Pêgo, A.P. (Acta BiomaterialiaActa Biomater., 2009)
Chitosan was functionalized with imidazole moieties (CHimi) with the aim of improving its buffering capacity and promoting the endosomal escape ability of chitosan-DNA complexes, ultimately increasing their transfection efficiency. 5.6%, 12.9% and 22.1% of the glucosamine residues of chitosan were substituted. Complexes with different molar ratios of primary amines to DNA phosphate anion (N/P) were prepared by a coacervation method. For an N/P > 3, CHimi polymers are able to complex electrostatically with DNA and condense it into positively charged nanostructures (average size 260 nm and zeta potential +16 mV at pH 5.5). In the concentration range 2.5-100 μg ml
Cited By (since 1996): 17Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2009.04.021PubMed ID: 19427930Language of Original Document: EnglishCorrespondence Address: Pêgo, A.P.; INEB-Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: apego@ineb.up.ptChemicals/CAS: DNA, 9007-49-2; chitosan, 9012-76-4; imidazole, 1467-16-9, 288-32-4; Biocompatible Materials; Buffers; Chitosan, 9012-76-4; DNA, 9007-49-2; Drug CarriersReferences: Kirkpatrick, C.J., Fuchs, S., Peters, K., Brochhausen, C., Hermanns, M.I., Unger, R.E., Visions for regenerative medicine: interface between scientific fact and science fiction (2006) Artif Organs, 30, pp. 822-827;Simões, S., Filipe, A., Faneca, H., Mano, M., Penacho, N., Duzgunes, N., Cationic liposomes for gene delivery (2005) Expert Opin Drug Deliv, 2, pp. 237-254; Lungwitz, U., Breunig, M., Blunk, T., Gopferich, A., Polyethylenimine-based non-viral gene delivery systems (2005) Eur J Pharm Biopharm, 60, pp. 247-266; Filion, M.C., Phillips, N.C., Major limitations in the use of cationic liposomes for DNA delivery (1998) Int J Pharm, 162, pp. 159-170; Lv, H., Zhang, S., Wang, B., Cui, S., Yan, J., Toxicity of cationic lipids and cationic polymers in gene delivery (2006) J Control Release, 114, pp. 100-109; Itaka, K., Ohba, S., Miyata, K., Kawaguchi, H., Nakamura, K., Takato, T., Bone regeneration by regulated in vivo gene transfer using biocompatible polyplex nanomicelles (2007) Mol Ther, 15, pp. 1655-1662; Borchard, G., Chitosans for gene delivery (2001) Adv Drug Deliv Rev, 52, pp. 145-150; Khalil, I.A., Kogure, K., Akita, H., Harashima, H., Uptake pathways and subsequent intracellular trafficking in nonviral gene delivery (2006) Pharmacol Rev, 58, pp. 32-45; Behr, J.P., The proton sponge: a trick to enter cells the viruses did not exploit (1997) Chimia, 51, pp. 34-36; Kim, T.H., Kim, S.I., Akaike, T., Cho, C.S., Synergistic effect of poly(ethylenimine) on the transfection efficiency of galactosylated chitosan/DNA complexes (2005) J Control Release, 105, pp. 354-366; Midoux, P., Monsigny, M., Efficient gene transfer by histidylated polylysine/pDNA complexes (1999) Bioconjug Chem, 10, pp. 406-411; Benns, J.M., Choi, J.S., Mahato, R.I., Park, J.S., Kim, S.W., pH-sensitive cationic polymer gene delivery vehicle: N-Ac-poly(l-histidine)-graft-poly(l-lysine) comb shaped polymer (2000) Bioconjug Chem, 11, pp. 637-645; Putnam, D., Gentry, C.A., Pack, D.W., Langer, R., Polymer-based gene delivery with low cytotoxicity by a unique balance of side-chain termini (2001) Proc Natl Acad Sci USA, 98, pp. 1200-1205; Dubruel, P., Christiaens, B., Vanloo, B., Bracke, K., Rosseneu, M., Vandekerckhove, J., Physicochemical and biological evaluation of cationic polymethacrylates as vectors for gene delivery (2003) Eur J Pharm Sci, 18, pp. 211-220; Dubruel, P., Dekie, L., Schacht, E., Poly-l-glutamic acid derivatives as multifunctional vectors for gene delivery. Part A. Synthesis and physicochemical evaluation (2003) Biomacromolecules, 4, pp. 1168-1176; Kim, T.H., Ihm, J.E., Choi, Y.J., Nah, J.W., Cho, C.S., Efficient gene delivery by urocanic acid-modified chitosan (2003) J Control Release, 93, pp. 389-402; Dubruel, P., Christiaens, B., Rosseneu, M., Vandekerckhove, J., Grooten, J., Goossens, V., Buffering properties of cationic polymethacrylates are not the only key to successful gene delivery (2004) Biomacromolecules, 5, pp. 379-388; Juusola, P., Minkkinen, P., Leino, L., Laihia, J.K., Determination of the dissociation constants of urocanic acid isomers in aqueous solutions (2007) Monatsh Chem, 138, pp. 951-965; Roberts, J.D., Yu, C., Flanagan, C., Birdseye, T.R., A nitrogen-15 nuclear magnetic resonance study of the acid-base and tautomeric equilibria of 4-substituted imidazoles and its relevance to the catalytic mechanism of alfa-lytic protease (1982) J Am Chem Soc, 104, pp. 3945-3949; Roberts, G.A.F., (1992) Chitin chemistry, , Palgrave Macmillan, London; Nakagawa, Y., Murai, T., Hasegawa, C., Hirata, M., Tsuchiya, T., Yagami, T., Endotoxin contamination in wound dressings made of natural biomaterials (2003) J Biomed Mater Res B Appl Biomater, 66, pp. 347-355; (1987) Guideline on validation of the limulus amebocyte lysate test as an end-product endotoxin test for human and animal parenteral drugs, biological products, and medical devices, , U.S. Department of Health and Human Services, Public Health Service, Food and Drug Administration; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., Molecular parameters of chitosans depolymerized with the aid of papain (1996) Carbohydr Polym, 29, pp. 63-68; Sehgal, D., Vijay, I.K., A method for the high-efficiency of water-soluble carbodiimide-mediated amidation (1994) Anal Biochem, 218, pp. 87-91; Leong, K.W., Mao, H.Q., Truong-Le, V.L., Roy, K., Walsh, S.M., August, J.T., DNA-polycation nanospheres as non-viral gene delivery vehicles (1998) J Control Release, 53, pp. 183-193; Lee, M., Nah, J.W., Kwon, Y., Koh, J.J., Ko, K.S., Kim, S.W., Water-soluble and low molecular weight chitosan-based plasmid DNA delivery (2001) Pharm Res, 18, pp. 427-431; van Kuppeveld, F.J., van der Logt, J.T., Angulo, A.F., van Zoest, M.J., Quint, W.G., Niesters, H.G., Genus- and species-specific identification of mycoplasmas by 16S rRNA amplification (1992) Appl Environ Microbiol, 58, pp. 2606-2615; van Kuppeveld, F.J., van der Logt, J.T., Angulo, A.F., van Zoest, M.J., Quint, W.G., Niesters, H.G., Genus- and species-specific identification of mycoplasmas by 16S rRNA amplification (1993) Appl Environ Microbiol, 59, p. 655; Mosmann, T., Rapid colorimetric assay for cellular growth and survival: application to proliferation and cytotoxicity assays (1983) J Immunol Methods, 65, pp. 55-63; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Godbey, W.T., Ku, K.K., Hirasaki, G.J., Mikos, A.G., Improved packing of poly(ethylenimine)/DNA complexes increases transfection efficiency (1999) Gene Ther, 6, pp. 1380-1388; Pouton, C.W., Lucas, P., Thomas, B.J., Uduehi, A.N., Milroy, D.A., Moss, S.H., Polycation-DNA complexes for gene delivery: a comparison of the biopharmaceutical properties of cationic polypeptides and cationic lipids (1998) J Control Release, 53, pp. 289-299; Mao, H.Q., Roy, K., Troung-Le, V.L., Janes, K.A., Lin, K.Y., Wang, Y., Chitosan-DNA nanoparticles as gene carriers: synthesis, characterization and transfection efficiency (2001) J Control Release, 70, pp. 399-421; Poole, B., Ohkuma, S., Effect of weak bases on the intralysosomal pH in mouse peritoneal-macrophages (1981) J Cell Biol, 90, pp. 665-669; Bowman, E.J., Siebers, A., Altendorf, K., Bafilomycins: a class of inhibitors of membrane ATPases from microorganisms, animal cells, and plant cells (1988) Proc Natl Acad Sci USA, 85, pp. 7972-7976; van Deurs, B., Holm, P.K., Sandvig, K., Inhibition of the vacuolar H+ATPase with bafilomycin reduces delivery of internalized molecules from mature multivesicular endosomes to lysosomes in HEp-2 cells (1996) Eur J Cell Biol, 69, pp. 343-350; Merdan, T., Kopecek, J., Kissel, T., Prospects for cationic polymers in gene and oligonucleotide therapy against cancer (2002) Adv Drug Deliv Rev, 54, pp. 715-758; Mansouri, S., Lavigne, P., Corsi, K., Benderdour, M., Beaumont, E., Fernandes, J.C., Chitosan-DNA nanoparticles as non-viral vectors in gene therapy: strategies to improve transfection efficacy (2004) Eur J Pharm Biopharm, 57, pp. 1-8; Erbacher, P., Zou, S.M., Bettinger, T., Steffan, A.M., Remy, J.S., Chitosan-based vector/DNA complexes for gene delivery: biophysical characteristics and transfection ability (1998) Pharm Res, 15, pp. 1332-1339; Kiang, T., Wen, J., Lim, H.W., Leong, K.W., The effect of the degree of chitosan deacetylation on the efficiency of gene transfection (2004) Biomaterials, 25, pp. 5293-5301; Ishii, T., Okahata, Y., Sato, T., Mechanism of cell transfection with plasmid/chitosan complexes (2001) BBA-Biomembranes, 1514, pp. 51-64; Lavertu, M., Methot, S., Tran-Khanh, N., Buschmann, M.D., High efficiency gene transfer using chitosan/DNA nanoparticles with specific combinations of molecular weight and degree of deacetylation (2006) Biomaterials, 27, pp. 4815-4824; de Smedt, S.C., Demeester, J., Hennink, W.E., Cationic polymer based gene delivery systems (2000) Pharm Res, 17, pp. 113-126; Kichler, A., Leborgne, C., Coeytaux, E., Danos, O., Polyethylenimine-mediated gene delivery: a mechanistic study (2001) J Gene Med, 3, pp. 135-144; Wattiaux, R., Laurent, N., Wattiaux-De Coninck, S., Jadot, M., Endosomes, lysosomes: their implication in gene transfer (2000) Adv Drug Deliv Rev, 41, pp. 201-208; Pelkmans, L., Helenius, A., Endocytosis via caveolae (2002) Traffic, 3, pp. 311-320; Felgner, P.L., Gadek, T.R., Holm, M., Roman, R., Chan, H.W., Wenz, M., Lipofection-a highly efficient, lipid-mediated DNA-transfection procedure (1987) Proc Natl Acad Sci USA, 84, pp. 7413-7417; Conner, S.D., Schmid, S.L., Regulated portals of entry into the cell (2003) Nature, 422, pp. 37-44; Koping-Hoggard, M., Tubulekas, I., Guan, H., Edwards, K., Nilsson, M., Varum, K.M., Chitosan as a nonviral gene delivery system. Structure-property relationships and characteristics compared with polyethylenimine in vitro and after lung administration in vivo (2001) Gene Ther, 8, pp. 1108-1121; Boussif, O., Zanta, M.A., Behr, J.P., Optimized galenics improve in vitro gene transfer with cationic molecules up to 1000-fold (1996) Gene Ther, 3, pp. 1074-1080
Keywords: article; beta galactosidase; Biocompatible Materials; Buffers; Cell Line; cell transport; Chemical structure; chitosan; coacervation; complex formation; controlled study; Cytotoxicity; Diffusion; DNA; Drug Carriers; Drug Compounding; endosome; Gene delivery; Gene transfer; genetic transfection; human; human cell; Humans; imidazole; Kidney; materials testing; nanomaterial; nanoparticle; priority journal; protein expression; proton transport; Tissue engineering; Transfection

In vitro biological characterization of macroporous 3D Bonelike ® structures prepared through a 3D machining technique - Laranjeira, M.S.; Dias, A.G.; Santos, J.D.; Fernandes, M.H. (Materials Science and Engineering CMater. Sci. Eng. C, 2009)
3D bioactive macroporous structures were prepared using a 3D machining technique. A virtual 3D structure model was created and a computer numerically controlled (CNC) milling device machined Bonelike ® samples. The resulting structures showed a reproducible macroporosity and interconnective structure. Macropores size after sintering was approximately 2000 μm. In vitro testing using human bone marrow stroma showed that cells were able to adhere and proliferate on 3D structures surface and migrate into all macropore channels. In addition, these cells were able to differentiate, since mineralized globular structures associated with cell layer were identified. Results obtained showed that 3D structures of Bonelike ® successfully allow cell migration into all macropores, and allow human bone marrow stromal cells to proliferate and differentiate. This innovative technique may be considered as a step-forward preparation for 3D interconnective macroporous structures that allow bone ingrowth while maintaining mechanical integrity. © 2008 Elsevier B.V. All rights reserved.
Keywords: 3-D structures; 3D machining techniques; Biological characterizations; Bone; Bone ingrowths; Bone marrow stroma cells; Bone substitute; Bonelike; Cell layers; Cell migrations; Computer control systems; cytology; Globular structures; Human bone marrow stromal cells; Human bone marrows; In-vitro; Machining; Macro porosities; Macro-pores; Macroporous; Macroporous structures; Mechanical integrities; Porous materials; Sintering; Surface testing; Three dimensional; ®

Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide - Martins, M.C.L.; Curtin, S.A.; Freitas, S.C.; Salgueiro, P.; Ratner, B.D.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2009)
Systemic heparinization, used during haemodialysis to prevent blood clotting on the extracorporeal circuit, leads to a high incidence of hemorrhagic complications. The adverse reactions associated with heparin neutralization using protamine sulphate justify the development of an alternative system for blood deheparinization. The main objective of this work is to design nanostructured surfaces with the capacity to bind heparin from blood in a selective way. A heparin-binding polypeptide, composed of L-lysine and L-leucine (pKL), was synthesized and immobilized, in different concentrations, onto self-assembled monolayers (SAMs) terminated with tetra(ethylene-glycol) (EG4 SAMs). Immobilization was performed using a fixed concentration of pKL after surface activation to different degrees using a range of CDI (N,N′-carbonyldiimidazole) concentrations. Results demonstrated that the presence of pKL increases heparin adsorption to EG4-SAMs, independently of the pKL concentration and the way of immobilization (adsorption or covalent bound). Selectivity towards heparin was successfully achieved on SAMs with low concentrations of immobilized pKL (9-17% of pKL). Surfaces were characterized using ellipsometry, contact angle measurements, Fourier transform infrared reflection absorption spectroscopy (IRAS), atomic force microscopy, and X-ray photoelectron spectroscopy. Heparin adsorption was assessed using IRAS and N-sulphonate- 35S-heparin. Therefore, this study could give a good contribution for the design of blood deheparinization devices. © 2008 Wiley Periodicals, Inc.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31849PubMed ID: 18286636Language of Original Document: EnglishCorrespondence Address: Martins, M. C. L.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomaterials, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180, Porto, Portugal; email: cmartins@ineb.up.ptChemicals/CAS: carbonyldiimidazole, 530-62-1; heparin, 37187-54-5, 8057-48-5, 8065-01-8, 9005-48-5; imidazole, 1467-16-9, 288-32-4; leucine, 61-90-5, 7005-03-0; lysine, 56-87-1, 6899-06-5, 70-54-2; tetraethylene glycol, 112-60-7; Ethylene Glycol, 107-21-1; Heparin, 9005-49-6; Leucine, 61-90-5; Lysine, 56-87-1; PeptidesReferences: Dailey J. Blood. Ipswich, MA, USA: Medical Consulting Group; 1998Section, V., Chronic intermittent haemodialysis and prevention of clotting in the extracorporal system (2002) Nephrol Dialysis Transplant, 17, pp. 63-71;Zhang, Y.H., Singh, V.K., Yang, V.C., Novel approach for optimizing the capacity and efficacy of a protamine filter for clinical extracorporeal heparin removal (1998) Asaio J, 44, pp. M368-M373; Tao, W., Deyo, D.J., Brunston, R.L., Vertrees, R.A., Zwischenberger, J.B., Extracorporeal heparin adsorption following cardiopulmonary bypass with a heparin removal device - An alternative to protamine (1998) Critical Care Med, 26, pp. 1096-1102; Ameer, G.A., Barabino, G., Sasisekharan, R., Harmon, W., Cooney, C.L., Langer, R., Ex vivo evaluation of a Taylor-Couette flow, immobilized heparinase I device for clinical application (1999) Proc Natl Acad Sci USA, 96, pp. 2350-2355; Ostuni, E., Yan, L., Whitesides, G.M., The interaction of proteins and cells with self-assembled monolayers of alkanethiolates on gold and silver (1999) Colloids Surf B-Biointerfaces, 15, pp. 3-30; Mrksich, M., Whitesides, G.M., Using self-assembled monolayers that present oligo(ethylene glycol) groups to control the interactions of proteins with surfaces. Poly(Ethylene Glycol) (1997) ACS Symposium Series, 680, pp. 361-373; Cardin, A.D., Weintraub, H.J.R., Molecular modeling of proteinglycosaminoglycan interactions (1989) Arteriosclerosis, 9, pp. 21-32; Kricheldorf, H.R., (1987) α-Amino Acid N-Carboxyanhydrides and Related Heterocycles, , New York: Springer Verlag;; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methylterminated alkanethiols self-assembled monolayers (2003) J Biomed Mater Res A, 67, pp. 158-171; Lee, H.J., Nedelkov, D., Corn, R.M., Surface plasmon resonance imaging measurements of antibody arrays for the multiplexed detection of low molecular weight protein biomarkers (2006) Anal Chem, 78, pp. 6504-6510; Roeges, N.P.G., (1994) A Guide to the Complete Interpretation of Infrared Spectra of Organic Structures, , England: Wiley;; Li, L.Y., Chen, S.F., Zheng, J., Ratner, B.D., Jiang, S.Y., Protein adsorption on oligo(ethylene glycol)-terminated alkanethiolate self-assembled monolayers: The molecular basis for non-fouling behavior (2005) J Phys Chem B, 109, pp. 2934-2941; Beamson, G., High, B.D., (1992) Resolution XPS of Organic Polymers, , Chichester: Wiley;; Sousa, S.R., Moradas, F.P., Saramago, B., Viseu, M.L., Barbosa, M.A., Human serum albumin adsorption on TiO2 from single protein solutions and from plasma (2004) Langmuir, 20, pp. 9745-9754; Socrates, G., (2001) Infrared and Raman Characteristic Group Frequencies: Tables and Charts, , Chichester: Wiley;; Capila, I., Linhardt, R.J., Heparin - Protein interactions (2002) Angewandte Chemie-Int Ed, 41, pp. 391-112; Snell, C.R.F.G., Kinetics and thermodynamics of the alpha Helix - β Transconformation of poly(L-lysine) and L-leucine copolymers. A compensation phenomenon (1973) Biochemistry, 12, pp. 1017-1025; Hearn, M.T.W., 1,1′-Carbonyldiimidazole-mediated immobilization of enzymes and affinity ligands (1987) Methods Enzymol, 135, pp. 102-117; Stollner, D., Scheller, F.W., Warsinke, A., Activation of cellulose membranes with 1,1′-carbonyldiimidazole or 1-cyano-4-dimethylaminopyridinium tetrafluoroborate as a basis for the development of immunosensors (2002) Anal Biochem, 304, pp. 157-165
Keywords: Absorption spectroscopy; Adsorption; Alternative systems; Amines; Amino acids; Angle measurement; article; Atomic force microscopy; Atomic forces; Atomic spectroscopy; Binding peptides; Blood; Blood clotting; Carbonyl diimidazole; Carbonyldiimidazole; Contact angle; deheparinization; device; Dialysis; Electron energy levels; ellipsometry; Ethylene; Ethylene Glycol; Fourier Transform Infrared; Fourier transforms; Glycols; Haemodialysis; heparin; heparin binding protein; Heparinization; High incidences; Humans; imidazole; immobilization; infrared spectroscopy; leucine; Low concentrations; lysine; Methods; Missile bases; Monolayers; nanomaterial; Nanostructured surfaces; Nanostructures; Peptide immobilization; Peptides; Photoelectron spectroscopy; Polysaccharides; Protein adsorption; protein binding; Renal Dialysis; Self assembled monolayers; Self-assembled monolayers; Sulphate; Surface activations; Surface functionalization; Surface Properties; surface property; tetraethylene glycol; unclassified drug; X ray photoelectron spectroscopy; X-ray photoelectron spectroscopies

Neural cell growth on TiO 2 anatase nanostructured surfaces - Collazos-Castro, J.E.; Cruz, A.M.; Carballo-Vila, M.; Lira-Cantú, M.; Abad, L.; del Pino, Á.P.; Fraxedas, J.; San Juan, A.; Fonseca, C.; Pêgo, A.P.; Casañ-Pastor, N. (Thin Solid FilmsThin Solid Films, 2009)
Titanium oxides have anti-inflammatory activity and tunable electrochemical properties that make them attractive materials for biomedical applications. This work investigated the compatibility of nanometric coatings of low-temperature phases of TiO 2 with neurons in 4-day and 10-day cultures, using different cell densities to quantify cell survival and neurite extension. TiO 2 films were prepared by sol-gel and thermal treatment (250-450 °C) of hydrolyzed titanium tetra-isopropoxide on electrically conducting or insulating slides. The conducting substrates were not passivated by the nanometric oxide layer and could be used as electrodes. Characterization of the films showed nano-structured TiO 2 containing exclusively Ti +4 valence in anatase and amorphous phases. When coated with polylysine, all films permitted good neuron attachment and survival for at least ten days in culture. However, they generally reduced neurite growth compared to cell culture borosilicate glass, with dendrites more affected than axons. The analyses of surface topography, hydrophilicity, charge and chemical composition revealed that TiO 2 chemistry was the main factor responsible for neurite inhibition. © 2009 Elsevier B.V. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: THSFAdoi: 10.1016/j.tsf.2009.06.048Language of Original Document: EnglishCorrespondence Address: Casañ-Pastor, N.; Instituto de Ciencias de Materiales de Barcelona, CSIC, Campus la Universidad Autonoma Barcelona, E-08193 Barcelona, Spain; email: nieves@icmab.esReferences: Suzuki, R., Frangos, J.Á., (2000) Clin. Orthop. Relat. Res., 372, p. 280;Suzuki, R., Muyco, J., McKittrick, J., Frangos, J.A., (2003) J. Biomed. Mater. Res. A, 66, p. 396; Ulbrich, M.H., Fromherz, P., (2005) Appl. Phys. A., 81, p. 887; Topoglidis, E., Lutz, T., Willis, R.L., Barnett, C.J., Cass, A.E., Durrant, J.R., (2000) Faraday Discuss., 116, p. 35; Smith, J.R., Walsh, F.C., Clarke, R.L., (1998) J. Appl. Electrochem., 28, p. 1021; Dinh, N.N., Oan, N.T., Long, P.D., Bernard, M.N., Hugot-Le Goffb, A., (2003) Thin Solid Films, 423, p. 70; (2001) Titanium in Medicine, , Brunette D.M., Tengvall P., Textor M., and Thomsen P. (Eds), Springer-Verlag, Berlin; Textor, M., Sittig, C., Frauchiger, V., Tosatti, S., Brunette, D.M., (2001) Titanium in Medicine, 171. , Brunette D.M., Tengvall P., Textor M., and Thomsen P. (Eds), Springer-Verlag, Berlin; Contreras, R., Sahlin, H., Frangos, J.Á., (2007) J. Biomed. Mater. Res. A, 80, p. 480; Kolbrecka, K., Przyluski, J., (1994) Electrochim. Acta, 39, p. 1591; Diebold, U., (2003) Surf. Sci. Rep., 48, p. 53; Jeong, B.S., Norton, D.P., Budai, J.D., (2003) Solid-State Electron., 47, p. 2275; Moulton, S.E., Barisci, J.N., Bath, A., Stella, R., Wallace, G.C., (2005) Langmuir, 21, p. 316; Jackson, D.R., Omanovic, S., Roscoe, S.G., (2005) Langmuir, 16, p. 5449; Subramanian, V., Karki, A., Gnanasekar, K.I., Eddy, FP., Rambabu, B., (2006) J. Power Sources, 159, p. 186; Carballo-Vila, M., Moreno-Burriel, B., Jurado, J.R., Chinarro, E., Casañ-Pastor, N., Collazos-Castro, J.E., (2009) J. Biomed. Mater. Res. A, 90, p. 94; Brewer, G.J., Torricelli, J.R., Evege, E.K., Price, P.J., (1993) J. Neurosci. Res., 35, p. 567; Rajnicek, A.M., Britland, S., McCaig, C.D., (1997) J. Cell Sci., 110, p. 2905; Bao, W., Thullberg, M., Zhang, H., Onischenko, A., Strömblad, S., (2002) Mol. Cell. Biol., 22, p. 4587; Sanjana, N.E., Fuller, S.B., (2004) J. Neurosci. Methods, 136, p. 151; Parak, W.J., George, M., Kudera, M., Gaub, H.E., Behrends, J.C., (2001) Eur. Biophys. J., 29, p. 607; Dotti, C.G., Sullivan, C.A., Banker, G.A., (1988) J. Neurosci., 8, p. 1454; Davenport, R.W., McCaig, C.D., (1993) J. Neurobiology, 24, p. 89; Chuckowree, J.A., Vickers, J.C., (2003) J. Neurosci., 23, p. 3715; Long, T.C., Saleh, N., Tilton, R.D., Lowry, G.V., Veronesi, B., (2006) Environ. Sci. Technol., 40, p. 4346; Zhao, L., Chang, J., Zhai, W., (2005) J. Biomater. Appl., 19, p. 237; Swamy, V., Kusnetzov, A., Dubrovinsky, L.S., Caruso, R.A., Shchukin, D.G., Muddle, B.C., (2005) Phys. Rev., B, 71, p. 1; Lozano, M.P., Fraxedas, J., (2000) Surf. Interface Anal., 30, p. 623; Martínez-Ferrero, E., Sakatani, Y., Boissière, C., David Grosso, D., Fuertes, A., Fraxedas, J., Sánchez, C., (2007) Adv. Funct. Mater., 17, p. 3348; Roddick-Lanzilotta, A.D., McQuillan, A.J., (1999) J. Colloid Interface Sci., 217, p. 194; Kosmulski, M., (2002) Adv. Colloid Interface Sci., 99, p. 255; Ikegaya, Y., Itsukaichi-Nishida, Y., Ishihara, M., Tanaka, D., Matsuki, N., (2000) Neuroscience, 97, p. 215; Cyster, L.A., Parker, K.G., Parker, T.L., Grant, D.M., (2004) Biomaterials, 25, p. 97; Blau, A., Weinl, C., Mack, J., Kienle, S., Jung, G., Ziegler, C., (2001) J. Neurosci. Methods, 112, p. 65; Kommireddy, D.S., Sriram, S.M., Lvov, Y.M., Mills, D.K., (2006) Biomaterials, 27, p. 4296; Cai, K., Bossert, J., Jandt, K.D., (2006) Colloids Surf., B, 49, p. 136; Wang, Y.-X., Robertson, J.L., Spillman Jr., W.B., Claus, R.O., (2004) Pharm. Res., 21, p. 1362; Greve, F., Frerker, S., Bittermann, A.G., Burkhardt, C., Hierlemann, A., Hall, H., (2007) Biomaterials, 28, p. 5246; Yang, H., Fung, S.-Y., Pritzker, M., Chen, P., (2007) PLoS ONE, 2, pp. e1325; Giovambattista, N., Debenedetti, P.G., Rosky, P.J., (2007) J. Phys. Chem. B, 111, p. 9581; Onur, M.A., Taş, Z., Gürpnar, A., Şahin, A., Çehreli, M.C., (2004) Clin. Oral Implants Res., 15, p. 513; Lopez, T., Ortiz-Islas, E., Manjarrez, J., Rodríguez-Reinoso, F., Sepúlveda, A., Gonzalez, R.D., (2006) Opt. Mater., 29, p. 70
Keywords: Amorphous phasis; Anatase; Anti-inflammatory activity; Biomedical applications; Borosilicate glass; Cell culture; cell density; Cell membranes; cell survival; Chemical compositions; Coatings; Conducting substrates; Conductive films; Electrochemical properties; Gelation; Growth kinetics; Heat treatment; Iso-propoxide; Low temperature phasis; Nano-structured; Nanometrics; Nanostructured surface; Nanostructures; Neural cell; Neural cells; Neurite extension; Neurite growth; Neurites; Neurons; Oxide layer; polylysine; Surface topography; Thermal treatment; TiO; Titanium; Titanium dioxide; Titanium oxide; Titanium oxides

NPY revealed as a critical modulator of osteoblast function in vitro: New insights into the role of Y1 and Y2 receptors - Teixeira, L.; Sousa, D.M.; Nunes, A.F.; Sousa, M.M.; Herzog, H.; Lamghari, M. (Journal of Cellular BiochemistryJ. Cell. Biochem., 2009)
Neuropeptide Y (NPY) has recently emerged as a potential regulator of bone homeostasis. However, the relevance of NPY's role in osteoblast activity and the biological functions involving NPY receptors in bone homeostasis remain to be clarified. Here we report that chronically elevated NPY levels leaded to a modulation of the level of Y2 receptor expression marked with a transient down and upregulation according to the stage of osteoblast differentiation. We also show that NPY is a negative regulator of Y1 receptor expression. The pharmalogical activation of Y2 receptor with its agonist resulted in similar effect. Functional analysis also revealed the osteogenic potential of NPY with osteoblast phenotype markers being significantly enhanced in osteoprogenitor cells stimulated by NPY, probably due to the down-regulation of Y1 receptor. In contrasts, these cells exhibit a reduction in calcium deposition in extracellular matrix most likely mediated via Y2 receptor signalling. Furthermore, we show that NPY modulates receptor activator of nuclear factor kB (NF-kB) (RANK) ligand and osteoprotegerin, two key factors regulating bone remodelling. Specifically, NPY inhibits the transcriptional activity of RANKL promoter in osteoprogenitor cells and enhances OPG expression in osteoblasts at early stages of differentiation. However, NPY effect on OPG seemed to be unrelated to Y2 receptor activation. Taken together the present data supported the contribution of NPY pathway in bone homeostasis via a direct action on osteoblasts cells. © 2009 Wiley-Liss, Inc.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: JCEBDdoi: 10.1002/jcb.22194PubMed ID: 19459152Language of Original Document: EnglishCorrespondence Address: Lamghari, M.; Instituto de Engenharia Biomédica (INEB), Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: lamghari@ineb.up.ptChemicals/CAS: calcium, 14092-94-5, 7440-70-2; osteoclast differentiation factor, 200145-93-3; osteoprotegerin, 205944-50-9; Alkaline Phosphatase, 3.1.3.1; Neuropeptide Y; Osteoprotegerin; RANK Ligand; Receptors, Neuropeptide YReferences: Ahmed, M., Srinivasan, G.R., Theodorsson, E., Bjurholm, A., Kreicbergs, A., Extraction and quantitation of neuropeptides in bone by radioimmunoassay (1994) Regul Pept, 51, pp. 179-188;Allison, S.J., Herzog, H., NPY and bone (2006) EXS, 95, pp. 171-182; Allison, S.J., Baldock, P., Sainsbury, A., Enriquez, R., Lee, N.J., Lin, E.J., Klugman, M., Gardiner, E.M., Conditional deletion of hypothalamic Y2 receptors reverts gonadectomy-induced bone loss in adult mice (2006) J Biol Chem, 281, pp. 23436-23444; Amano, S., Arai, M., Goto, S., Togari, A., Inhibitory effect of NPY on isoprenaline-induced osteoclastogenesis in mouse bone marrow cells (2007) Biochim Biophys Acta, 1770, pp. 966-973; Baldock, P.A., Sainsbury, A., Couzens, M., Enriquez, R.F., Ghomas, G.P., Gardiner, E.M., Herzog, H., Hypothalamic Y2 receptors regulate bone formation (2002) J Clin Investig, 109, pp. 915-921; Baldock, P.A., Sainsbury, A., Allison, S., Lin, E.J., Couzens, M., Boey, D., Enriquez, R., Gardiner, E.M., Hypothalamic control of bone formation: Distinct actions of leptin and y2 receptor pathways (2005) J Bone Miner Res, 20, pp. 1851-1857; Baldock, P.A., Allison, S.J., Lundberg, P., Lee, N.J., Slack, K., Lin, E.J., Enriquez, R.F., Herzog, H., Novel role of Y1 receptors in the coordinated regulation of bone and energy homeostasis (2007) J Biol Chem, 282, pp. 19092-19102; Chenu, C., Role of innervation in the control of bone remodelling (2004) J Musculoskel Neuron Interact, 4, pp. 132-134; Chenu, C., Marenzana, M., Sympathetic nervous system and bone remodeling (2005) Joint Bone Spine, 72, pp. 481-483; Clark, J.T., Kalra, P.S., Kalra, S.P., Neuropeptide Y stimulates feeding but inhibits sexual behavior in rats (1985) Endocrinology, 117, pp. 2435-2442; Dumont, Y., Jacques, D., Bouchard, P., Quirion, R., Species differences in the expression and distribution of the neuropeptide Y Y1, Y2, Y4, and Y5 receptors in rodents, guinea pig, and primates brains (1998) J Comp Neurol, 402, pp. 372-384; Elefteriou, F., Neuronal signalling and the regulation of bone remodelling (2005) Cell Mol Life Sci, 62, pp. 2339-2349; Ericsson, A., Schalling, M., McIntyre, K.R., Lundberg, J.M., Larhammar, D., Seroogy, K., Hokfelt, T., Persson, H., Detection of neuropeptide Y and its mRNA in megakaryocytes: Enhanced levels in certain autoimmune mice (1987) Proc Natl Acad Sci USA, 84, pp. 5585-5589; Fu, Q., Manolagas, S.C., O'Brien, C.A., Parathyroid hormone controls receptor activator of NF-kappaB ligand gene expression via a distant transcriptional enhancer (2006) Mol Cell Biol, 26, pp. 6453-6468; Gori, F., Hofbauer, L.C., Dunstan, C.R., Spelsberg, T.C., Khosla, S., Riggs, B.L., The expression of osteoprotegerin and RANK ligand and the support of osteoclast formation by stromal-osteoblast lineage cells is developmentally regulated (2000) Endocrinology, 141, pp. 4768-4776; Herzog, H., Neuropeptide Y and energy homeostasis: Insights from Y receptor knockout models (2003) Eur J Pharmacol, 480 (1-3), pp. 21-29; Hill, E.L., Turner, R., Elde, R., Effects of neonatal sympathectomy and capsaicin treatment on bone remodeling in rats (1991) Neuroscience, 44 (3), pp. 747-755; Holliday, N.D., Michel, M.C., Cox, H.M., NPY receptor subtypes and their signal transduction (2004) Neuropeptide Y and related peptides, Handbook of experimental pharmacology, 162, pp. 45-74. , Michel MC, editor, Berlin: Springer-Verlag, Heidelberg, pp; Hosaka, H., Nagata, A., Yoshida, T., Shibata, T., Nagao, T., Tanaka, T., Saito, Y., Tatsuno, I., Pancreatic polypeptide is secreted from and controls differentiation through its specific receptors in osteoblastic MC3T3-E1 cells (2008) Peptides, 29 (8), pp. 1390-1395; Imai, S., Matsusue, Y., Neuronal regulation of bone metabolism and anabolism: Calcitonin gene-related peptide-, substance P-, and tyrosine hydroxylase-containing nerves and the bone (2002) Microsc Res Tech, 58, pp. 61-69; Kondo, H., Guo, J., Bringhurst, F.R., Cyclic adenosine monophosphate/protein kinase A mediates parathyroid hormone/parathyroid hormone-related protein receptor regulation of osteoclastogenesis and expression of RANKL and osteoprotegerin mRNAs by marrow stromal cells (2002) J Bone Miner Res, 17, pp. 1667-1679; Kuo, L.E., Kitlinska, J.B., Tilan, J.U., Li, L., Baker, S.B., Johnson, M.D., Lee, E.W., Zukowska, Z., Neuropeptide Y acts directly in the periphery on fat tissue and mediates stress-induced obesity and metabolic syndrome (2007) Nat Med, 13, pp. 803-811; Lee, S.K., Lornezo, J.A., Regulation of receptor activator of nuclear factor-kappaB ligand and osteoprotegerin mRNA expression by parathyroid hormone is predominantly mediated by the protein kinase a pathway in murine bone marrow cultures (2002) Bone, 31, pp. 252-259; Lerner, U.H., Lundberg, P., Kinins, neuro-osteogenic factors (2002) Principles of bone biology, pp. 773-799. , Bilezikian JP, Raisz LG, Rodan GA, editors, 2nd edition. San Diego: Academic Press. pp; Li, J., Ahmad, T., Spetea, M., Ahmed, M., Kreicbergs, A., Bone reinnervation after fracture: A study in the rat (2001) J Bone Miner Res, 16, pp. 1505-1510; Lundberg, P., Lerner, U.H., Expression and regulatory role of receptors for vasoactive intestinal peptide in bone cells (2002) Microsc Res Tech, 58, pp. 98-103; Lundberg, P., Boström, I., Mukohyama, H., Bjurholm, A., Smans, K., Lerner, U.H., Neuro-hormonal control of bone metabolism: Vasoactive intestinal peptide stimulates alkaline phosphatase activity and mRNA expression in mouse calvarial osteoblasts as well as calcium accumulation mineralized bone nodules (1999) Regul Pept, 85, pp. 47-58; Lundberg, P., Allison, S.J., Lee, N.J., Baldock, P.A., Brouard, N., Rost, S., Enriquez, R.F., Herzog, H., Greater bone formation of Y2 knockout mice is associated with increased osteoprogenitor numbers and altered Y1 receptor expression (2007) J Biol Chem, 282, pp. 19082-19091; Michel, M.C., Beck-Sickinger, A., Cox, H., Doods, H.N., Herzog, H., Larhammar, D., Quirion, R., Westfall, T., XVI. International Union of Pharmacology recommendations for the nomenclature of neuropeptide Y, peptide YY, and pancreatic polypeptide receptors (1998) Pharmacol Rev, 50, pp. 143-150; Movafagh, S., Hobson, J.P., Spiegel, S., Kleinman, H.K., Zukowska, Z., Neuropeptide Y induces migration, proliferation, and tube formation of endothelial cells bimodallyvia Y1, Y2, and Y5 receptors (2006) FASEB J, 20, pp. 1327-1337; Sainsbury, A., Baldock, P.A., Schwarzer, C., Ueno, N., Enriquez, R.F., Couzens, M., Inui, A., Gardiner, E.M., Synergistic effects of Y2 and Y4 receptors on adiposity and bone mass revealed in double knockout mice (2003) Mol Cell Biol, 23, pp. 5225-5233; Serre, C.M., Farlay, D., Delmas, P.D., Chenu, C., Evidence for a dense and intimate innervation of the bone tissue, including glutamate-containing fibers (1999) Bone, 25, pp. 623-629; Simonet, W.S., Lacey, D.L., Dunstan, C.R., Kelley, M., Chang, M.S., Lüthy, R., Nguyen, H.Q., Boyle, W.J., Osteoprotegerin: A novel secreted protein involved in the regulation of bone density (1997) Cell, 89, pp. 309-319; Sudo, H., Kodama, H.A., Amagai, Y., Yamamoto, S., Kasai, S., In vitro differentiation and calcification in a new clonal osteogenic cell line derived from newborn mouse calvaria (1983) J Cell Biol, 96, pp. 191-198; Szczesny, G., Molecular aspects of bone healing, remodelling (2002) Pol J Pathol, 53, pp. 145-153; Tatemoto, K., Neuropeptide Y: Complete amino acid sequence of the brain peptide (1982) Proc Natl Acad Sci USA, 79, pp. 5485-5489; Thiriet, N., Deng, X., Solinas, M., Ladenheim, B., Curtis, W., Goldberg, S.R., Palmiter, R.D., Cadet, J.L., Neuropeptide Y protects against methamphetamine-induced neuronal apoptosis in the mouse striatum (2005) J Neurosci, 25, pp. 5273-5279; Wittmann, W., Loacker, S., Kapeller, I., Herzog, H., Schwarzer, C., Y1-receptors regulate the expression of Y2-receptors in distinct mouse forebrain areas (2005) Neuroscience, 136, pp. 241-250; Wortley, K.E., Garcia, K., Okamoto, H., Thabet, K., Anderson, K.D., Shen, V., Herman, J.P., Sleeman, M.W., Peptide YY regulates bone turnover in rodents (2007) Gastroenterology, 133, pp. 1534-1543
Keywords: alkaline phosphatase; animal cell; animal tissue; Animals; article; Bone; Bone Marrow Cells; bone remodeling; Calcium; cell activity; cell differentiation; cell function; Cell Line; cell stimulation; controlled study; down regulation; extracellular matrix; gene expression regulation; genetic transcription; Homeostasis; immunoglobulin enhancer binding protein; in vitro study; Mice; neuropeptide Y; neuropeptide Y1 receptor; neuropeptide Y2 receptor; nonhuman; NPY; nuclear factor Y; osteoblast; Osteoblasts; osteoclast differentiation factor; Osteoprotegerin; phenotype; priority journal; promoter region; protein expression; RANK Ligand; Receptors, Neuropeptide Y; Reverse Transcriptase Polymerase Chain Reaction; signal transduction; stem cell; Stromal Cells; upregulation; Y1 receptor; Y2 receptor

NPY signalling pathway in bone homeostasis: Y1 receptor as a potential drug target - Sousa, D.M.; Herzog, H.; Lamghari, M. (Current Drug TargetsCurr. Drug Targets, 2009)
Neuropeptide (NPY) is a neurotransmitter widely distributed in central and peripheral nervous system that has been implicated in several physiological processes through activation of five different Y receptors: Y1, Y2, Y4, Y5, and y6. NPY system has been extensively studied for the last decades due to its implications in a wide variety of physiological processes. For this purpose a diversity of sophisticated animal models and receptors agonists and antagonists has been developed to better understand its actions throughout body homeostasis. Consequently, NPY and its receptors have recently emerged as a potential regulator of bone homeostasis. This is supported by the demonstration of an increase of bone mass in mice lacking Y1 or Y2 receptor genes. Recent findings revealed Y1 receptor as a potential drug target candidate for prevention and treatment of bone loss. Indeed, it has been demonstrated that osteoblasts express Y1 receptor while no other Y receptor was detected in these cells, implicating Y1 receptor signalling in the local control of bone turnover. In this review, we have summarized the findings obtained from studies on NPY system in skeletogenesis focusing on Y1 receptor. © 2009 Bentham Science Publishers Ltd.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: CDTUAdoi: 10.2174/138945009787122888Language of Original Document: EnglishCorrespondence Address: Lamghari, M.; INEB - Instituto de Engenharia Biomédica, Universidade do Porto, NEWTherapies Group, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: lamghari@ineb.up.ptChemicals/CAS: gr 231118, 158859-98-4; n [1 [4 [[[[4 [(dimethylamino)methyl]cyclohexyl]methyl]amino]iminomethyl]benzyl] 2 oxo 2 (1 pyrrolidinyl)ethyl] alpha [(2 naphthalenylsulfonyl)amino]benzenepropanamide, 163238-19-5; n2 diphenylacetyl n (4 ureidomethylbenzyl)argininamide, 191868-14-1, 217977-06-5; nalpha (diphenylacetyl) n (4 hydroxybenzyl) dextro argininamide, 159013-54-4; neuropeptide Y, 82785-45-3, 83589-17-7; peptide YY, 81858-94-8; Ligands; Neuropeptide Y; Receptors, Neuropeptide YTradenames: bibo 3304; bibp 3226; gi 264879a; gr 231118; gw 1229; j 115814; ly 357897; sr 120819aReferences: Lundberg, P., Lerner, U.H., (2002) Microsc. Res. Tech, 58 (2), pp. 98-103;Baldock, P.A., Sainsbury, A., Couzens, M., Enriquez, R.F., Thomas, G.P., Gardiner, E.M., Herzog, H., (2002) J. Clin. Invest, 109 (7), pp. 915-921; Baldock, P.A., Allison, S., McDonald, M.M., Sainsbury, A., Enriquez, R.F., Little, D.G., Eisman, J.A., Herzog, H., (2006) J. Bone Miner. Res, 21 (10), pp. 1600-1607; Tatemoto, K., Carlquist, M., Mutt, V., (1982) Nature, 296 (5858), pp. 659-660; Tatemoto, K., (1982) Proc. Natl. Acad. Sci. U.S.A, 79 (18), pp. 5485-5489; Larhammar, D., (1996) Regul. Pept, 62, pp. 1-11; Tatemoto, K., (1982) Proc. Natl. Acad. Sci. U.S.A, 79 (8), pp. 2514-2518; Kimmel, J.R., Hayden, J., Pollock, H.G., (1975) J. Biol. Chem, 250 (24), pp. 9369-9376; Michel, M.C., Beck-Sickinger, A., Cox, H., Doods, H.N., Herzog, H., Larhammar, D., Quirion, R., Westfall, T., (1998) Pharmacol. Rev, 50 (1), pp. 143-150; Fuhlendorff, J., Johansen, N.L., Melberg, S.G., Thogersen, H., And Schwartz, T.W., (1990) J. Biol. Chem, 265 (20), pp. 11706-11712; Blundell, T.L., Pitts, J.E., Tickle, I.J., Wood, S.P., Wu, C.W., (1981) Proc. Natl. Acad. Sci. U.S.A, 78 (7), pp. 4175-4179; Cerdá-Reverter, J., Larhammar, D., (2000) Biochem. Cell Biol, 78 (3), pp. 371-392; Allen, J., Novotný, J., Martin, J., Heinrich, G., (1987) Proc. Natl. Acad. Sci. U.S A, 84 (8), pp. 2532-2536; Wan, C.P., Lau, B.H.S., (1995) Life Sci, 56 (13), pp. 1055-1064; Schwartz, T.W., Fuhlendorff, J., Kjems, L.L., Kristensen, M.S., Vervelde, M., O'Hare, M., Krstenansky, J.L., Bjornholm, B., (1990) Ann. N.Y. Acad. Sci, 611, pp. 35-47; Nordmann, A., Blommers, M.J.J., Fretz, H., Arvinte, T., Drake, A.F., (1999) Eur. J. Biochem, 261 (1), pp. 216-226; Minth, C.D., Bloom, S.R., Polak, J.M., Dixon, J.E., (1984) Proc. Natl. Acad. Sci. U.S.A, 81 (14), pp. 4577-4581; Chronwall, B.M., DiMaggio, D.A., Massari, V.J., Pickel, V.M., Ruggiero, D.A., O'Donohue, T.L., (1985) Neuroscience, 15 (4), pp. 1159-1181; Wai, S.M., Kindler, P.M., Lam, E.T., Zhang, A., Yew, D.T., (2004) Cell Mol. Neurobiol, 24 (5), pp. 667-684; Sundler, F., Böttcher, G., Ekblad, E., Hakanson, R., (1993) The Biology of Neuropeptide Y and Related Peptides, pp. 157-196. , Colmers, W.F. and Wahlestedt, C, Ed, Humana Press, New Jersey, pp; Ekblad, E., Hakanson, R., Sundler, F., (1984) Regul. Pept, 10 (1), pp. 47-55; Cavadas, C., Silva, A.P., Mosimann, F., Cotrim, M.D., Ribeiro, C.A.F., Brunner, H.R., Grouzmann, E., (2001) J. Clin. Endocrinol. Metab, 86 (12), pp. 5956-5963; Silva, A.P., Cavadas, C., Grouzmann, E., (2002) Clin. Chim. Acta, 326 (1-2), pp. 3-25; Strand, F.L., (1999) Neuropeptides: Regulators of Physiological Processes, , MIT Press: Cambridge; Ericsson, A., Schalling, M., McIntrye, K.R., Lundberg, J.M., Larhammar, D., Seroogy, K., Hokfelt, T., Persson, H., (1987) Proc. Natl. Acad. Sci. U.S.A, 84 (16), pp. 5585-5589; Yang, K., Guan, H., Arany, E., Hill, D.J., Cao, X., (2008) FASEB J, 22 (7), pp. 2452-2464; Pedrazzini, T., Pralong, F., Grouzmann, E., (2003) Cell Mol. Life Sci, 60 (2), pp. 350-377; Blomqvist, A.G., Herzog, H., (1997) Trends Neurosci, 20 (7), pp. 294-298; Berglund, M.M., Schober, D.A., Statnick, M.A., McDonald, P.H., Gehlert, D.R., (2003) J. Pharmacol. Exp. Ther, 306 (1), pp. 147-156; Berglund, M., Hipskind, P., Gehlert, D., (2005) NPY Family of Peptides in Immune Disorders, Inflammation, Angiogenesis and Cancer, pp. 29-62. , Zukowska, Z. and Feuerstein, G.Z, Ed, Birkhaeuser Verlag, Switzerland, pp; Larhammar, D., Salaneck, E., (2004) Neuropeptides, 38 (4), pp. 141-151; Gregor, P., Feng, Y., DeCarr, L.B., Cornfield, L.J., McCaleb, M.L., (1996) J. Biol. Chem, 271 (44), pp. 27776-27781; Starbäck, P., Wraith, A., Eriksson, H., Larhammar, D., (2000) Biochem. Biophys. Res. Commun, 277 (1), pp. 264-269; Wraith, A., Törnsten, A., Chardon, P., Harbitz, I., Chowdhary, B.P., Andersson, L., Lundin, L.G., Larhammar, D., (2000) Genome Res, 10 (3), pp. 302-310; Larhammar, D., Wraith, A., Berglund, M.M., Holmberg, S.K.S., Lundell, I., (2001) Peptides, 22 (3), pp. 295-307; Larhammar, D., Blomqvist, A., Yee, F., Jazin, E., Yoo, H., Wahlested, C., (1992) Proc. Natl. Acad. Sci. U.S.A, 267 (16), pp. 10935-10938; Herzog, H., Hort, Y.J., Ball, H.J., Hayes, G., Shine, J., Selbie, L.A., (1992) Proc. Natl. Acad. Sci. U.S.A, 89 (13), pp. 5794-5798; Mullins, D.E., Zhang, X., Hawes, B.E., (2002) Regul. Pept, 105 (1), pp. 65-73; Krause, J., Eva, C., Seeburg, P.H., Sprengel, R., (1992) Mol. Pharmacol, 41 (5), pp. 817-821; Eva, C., Keinanen, K., Monyer, H., Seeburg, P., Sprengel, R., (1990) FEBS J, 271 (1-2), pp. 81-84; Nakamura, M., Sakanaka, C., Aoki, Y., Ogasawara, H., Tsuji, T., Kodama, H., Matsumoto, T., Noma, M., (1995) J. Biol. Chem, 270 (50), pp. 30102-30110; Álvaro, A.R., Martins, J., Araújo, I.M., Rosmaninho-Salgado, J., Ambrósio, A.F., Cavadas, C., (2008) J. Neurochem, , Epub ahead of print; Herzog, H., Baumgartner, M., Vivero, C., Selbie, L.A., Auer, B., Shine, J., (1993) J. Biol. Chem, 268 (9), pp. 6703-6707; Marklund, U., Byström, M., Gedda, K., Larefalk, A., Juneblad, K., Nyström, S., Ekstrand, A.J., (2002) Mol. Cell Endocrinol, 188 (1-2), pp. 85-97; Ball, H.J., Shine, J., Herzog, H., (1995) J. Biol. Chem, 270 (45), pp. 27272-27276; Ferguson, S.S., (2001) Pharmacol. Rev, 53 (1), pp. 1-24; Okamoto, T., Schlegel, A., Scherer, P.E., Lisanti, M.P., (1998) J. Biol. Chem, 273 (10), pp. 5419-5422; Fabry, M., Langer, M., Rothen-Rutishauser, B., Wunderli-Allenspach, H., Höcker, H., Beck-Sickinger, A.G., (2000) Eur. J. Biochem, 267 (17), pp. 5631-5637; Parker, S.L., Kane, J.K., Parker, M.S., Berglund, M.M., Lundell, I.A., Li, M.D., (2001) Eur. J. Biochem, 268 (4), pp. 877-886; Gicquiaux, H., Lecat, S., Gaire, M., Dieterlen, A., Mély, Y., Takeda, K., Bucher, B., Galzi, J.L., (2002) J. Biol. Chem, 277 (8), pp. 6645-6655; Ouedraogo, M., Lecat, S., Rochdi, M.D., Hachet-Haas, M., Matthes, H., Gicquiaux, H., Verrier, S., Bucher, B., (2008) Traffic, 9 (3), pp. 305-324; Holliday, N.D., Lam, C.W., Tough, I.R., Cox, H.M., (2005) Mol. Pharmacol, 67 (3), pp. 655-664; Broberger, C., Visser, T.J., Kuhar, M.J., Hökfelt, T., (1999) Neuroendocrinology, 70 (5), pp. 295-305; Kopp, J., Xu, Z.Q., Zhang, X., Pedrazzini, T., Herzog, H., Kresse, A., Wong, H., Hökfelt, T., (2002) Neurosci, 111 (3), pp. 443-532; Larsen, P.J., Tang-Christensen, M., Stidsen, C.E., Madsen, K., Smith, M.S., Cameron, J.L., (1999) J. Clin. Endocrinol. Metab, 84 (10), pp. 3781-3791; Wharton, J., Gordon, L., Byrne, J., Herzog, H., Selbie, L.A., Moore, K., Sullivan, M.H., Polak, J.M., (1993) Proc. Natl. Acad. Sci. U.S.A, 90 (2), pp. 687-691; Feth, F., Rascher, W., Michel, M.C., (1992) Br. J. Pharmacol, 105 (1), pp. 71-76; DiMaggio, D.A., Farah Jr, J.M., Westfall, T.C., (1994) Endocrinology, 134 (2), pp. 719-727; Dumont, Y., Quirion, R., (2006) Progress in Inflammation Research, pp. 7-33. , Feuernstein, G. and Zukowska-Grojec, Z, Ed, Birkhaeuser Verlag, Switzerland, pp; Balasubramaniam, A., (2003) Curr. Pharm. Des, 9 (15), pp. 1165-1175; Fuhlendorff, J., Gether, U., Aakerlund, L., Langeland-Johansen, N., Thogersen, H., Melberg, S.G., Olsen, U.B., Schwartz, T.W., (1990) Proc. Natl. Acad. Sci. U.S.A, 87 (1), pp. 182-186; Grandt, D., Feth, F., Rascher, W., Reeve Jr., J.R., Schlicker, E., Schimiczek, M., Layer, P., Michel, M.C., (1994) Eur. J. Pharmacol, 269 (2), pp. 127-132; Söll, R.M., Dinger, M.C., Lundell, I., Larhammer, D., Beck-Sickinger, A.G., (2001) Eur. J. Biochem, 268 (10), pp. 2828-2837; Mullins, D., Kirby, D., Hwa, J., Guzzi, M., Rivier, J., Parker, E., (2001) Mol. Pharmacol, 60 (3), pp. 534-540; Rudolf, K., Eberlein, W., Engel, W., Wieland, H.A., Willim, K.D., Entzeroth, M., Wienen, W., Doods, H.N., (1994) Eur. J. Pharmacol, 271 (2-3), pp. R11-R13; Wieland, H.A., Engel, W., Eberlein, W., Rudolf, K., Doods, H.N., (1998) Br. J. Pharmacol, 125 (3), pp. 549-555; Daniels, A.J., Matthews, J.E., Slepetis, R.J., Jansen, M., Viveros, O.H., Tadepalli, A., Harrington, W., Spaltenstein, A., (1995) Proc. Natl. Acad. Sci. U.S.A, 92 (20), pp. 9067-9071; Schober, D.A., Van Abbema, A.M., Smiley, D.L., Bruns, R.F., Gehlert, D.R., (1998) Peptides, 19 (3), pp. 537-542; Balasubramaniam, A., Dhawan, V.C., Mullins, D.E., Chance, W.T., Sheriff, S., Guzzi, M., Prabhakaran, M., Parker, E.M., (2001) J. Med. Chem, 44 (10), pp. 1479-1482; Daniels, A.J., Chance, W.T., Grizzle, M.K., Heyer, D., Matthews, J.E., (2001) Peptides, 22 (3), pp. 483-491; Hipskind, P.A., Lobb, K.L., Nixon, J.A., Britton, T.C., Bruns, R.F., Catlow, J., Dieckman-McGinty, D.K., Gehlert, D.R., (1997) J. Med. Chem, 40 (23), pp. 3712-3714; Schneider, E., Keller, M., Brennauer, A., Hoefelschweiger, B.K., Gross, D., Wolfbeis, O.S., Bernhardt, G., Buschauer, A., (2007) ChemBioChem, 8 (16), pp. 1981-1988; Serradeil-Le, G.C., Valeet, G., Rouby, P.E., Pellet, A., Oury-Donat, F., Brossard, G., Lespy, L., LeFur, G., (1995) FEBS Lett, 362 (2), pp. 192-196; Kanatani, A., Hata, M., Mashiko, S., Ishihara, A., Okamoto, O., Haga, Y., Ohe, T., Ihara, M., (2001) Mol. Pharmacol, 59 (3), pp. 501-505; Wahlestedt, C., Håkanson, R., (1986) Med. Biol, 64 (2-3), pp. 85-88; Doods, H.N., Wieland, H.A., Engel, W., Eberlein, W., Willim, K.D., Entzeroth, M., Wienen, W., Rudolf, K., (1996) Regul. Pept, 65 (1), pp. 71-77; Gerald, C., Walker, M.W., Criscione, L., Gustafson, E.L., Batzl-Hartmann, C., Smith, K.E., Vaysse, P., Weinshank, R.L., (1996) Nature, 382 (6587), pp. 168-171; Lin, S., Boey, D., Herzog, H., (2004) Neuropeptides, 38 (4), pp. 189-200; Pedrazzini, T., (2004) Neuropeptides, 38 (4), pp. 267-275; Pedrazzini, T., Seydoux, J., Künstner, P., Aubert, J.F., Grouzmann, E., Beermann, F., Brunner, H.R., (1998) Nat. Med, 4 (6), pp. 722-726; Kushi, A., Sasai, H., Koizumi, H., Takeda, N., Yokoyama, M., Nakamura, M., (1998) Proc. Natl. Acad. Sci. U.S.A, 95 (26), pp. 15659-15664; Naveilhan, P., Canals, J.M., Arenas, E., Ernfors, P., (2001) J. Neurochem, 78 (6), pp. 1201-1207; Thiele, T.E., Koh, M.T., Pedrazzini, T., (2002) J. Neurosci, 22 (3), pp. RC208-RC214; Karlsson, R.M., Choe, J.S., Cameron, H.A., Thorsell, A., Crawley, J.N., Holmes, A., Heilig, M., (2008) Psychopharmacology (Berlin, Ger.), 195 (4), pp. 547-557; Wheway, J., Mackay, C.R., Newton, R.A., Sainsbury, A., Boey, D., Herzog, H., Mackay, F., (2005) J. Exp. Med, 202 (11), pp. 1527-1538; Zukowska-Grojec, Z., Karwatowska-Prokopczuk, E., Fisher, T.A., Ji, H., (1998) Regul. Pept, 75-76, pp. 231-238; Hansel, D.E., Eipper, B.A., Ronnett, G.V., (2001) Nature, 410 (6831), pp. 940-944; Howell, O.W., Doyle, K., Goodman, J.H., Scharfman, H.E., Herzog, H., Pringle, A., Beck-Sickinger, A.G., Gray, W.P., (2005) J. Neurochem, 93 (3), pp. 560-570; Cho, Y.R., Kim, C.W., (2004) Biochem. Biophys. Res. Commun, 314 (3), pp. 773-780; Milenkovic, I., Weick, M., Wiedemann, P., Reichenbach, A., Bringmann, A., (2004) Graefe's Arch. Clin. Exp. Ophthalmol, 242 (11), pp. 944-950; Anitha, M., Chandrasekharan, B., Salgado, J.R., Grouzmann, E., Mwangi, S., Sitaraman, S.V., Srinivasan, S., (2006) Gastroenterology, 131 (4), pp. 1164-1178; Doyle, K.L., Karl, T., Hort, Y., Duffy, L., Shine, J., Herzog, H., (2008) J. Neurochem, 105 (3), pp. 641-652; Jacques, D., Abdel-Samad, D., (2007) Can. J. Physiol. Pharmacol, 85 (1), pp. 43-53; Agasse, F., Bernardino, L., Kristiansen, H., Christiansen, S.H., Ferreira, R., Silva, B., Grade, S., Malva, J.O., (2008) Stem Cells, 26 (6), pp. 1636-1645; Movafagh, S., Hobson, J.P., Spiegel, S., Kleinman, H.K., Zukowska, Z., (2006) FASEB J, 20 (11), pp. 1924-1926; Ruscica, M., Dozio, E., Boghossian, S., Bovo, G., Riaño, V.M., Motta, M., Magni, P., (2006) Endocrinology, 147 (3), pp. 1466-1473; Seger, R., Krebs, E.G., (1995) FASEB J, 9 (9), pp. 726-735; Kholodenko, B.N., (2002) Trends Cell Biol, 12 (4), pp. 173-177; Eva, C., Serra, M., Mele, P., Panzica, G.C., Oberto, A., (2006) Front. Neuroendocrinol, 27 (3), pp. 308-339; Elefteriou, F., Bone Cell Mol (2005) Life Sci, 62 (19-20), pp. 2339-2349; Chenu, C., (2004) J. Musculoskcl. Neuron. Interact, 4 (2), pp. 132-134; Allison, S.J., Baldock, P.A., Herzog, H., (2007) Peptides, 28 (2), pp. 320-325; Bjurholm, A., Kreicbergs, A., Terenius, L., Goldstein, M., Schultzberg, M., (1988) J. Auton. Nerv. Syst, 25 (2-3), pp. 119-125; Hill, E.L., Elde, R., (1991) Cell Tissue Res, 264 (3), pp. 469-480; Ahmad, T., Ugarph-Morawski, A., Li, J., Bileviciute-Ljungar, I., Finn, A., Ostenson, C.G., Kreicbergs, A., (2004) Regul. Pept, 119 (1-2), pp. 61-67; Togari, A., Arai, M., Mizutani, S., Mizutani, S., Koshihara, Y., Nagatsu, T., (1997) Neurosci. Lett, 233 (2-3), pp. 125-128; Lundberg, P., Allison, S.J., Lee, N.J., Baldock, P.A., Brouard, N., Rost, S., Enriquez, R.F., Herzog, H., (2007) J. Biol. Chem, 282 (26), pp. 19082-19091; Baldock, P.A., Sainsbury, A., Allison, S., Lin, E.J., Couzens, M., Boey, D., Enriquez, R., Gardiner, E.M., (2005) J. Bone Miner. Res, 20 (10), pp. 1851-1857; Ducy, P., Schinke, T., Karsenty, G., (2000) Science, 289 (5484), pp. 1501-1504; Takeda, S., Karsenty, G., (2001) J. Bone Miner. Metab, 19 (3), pp. 195-198; Ducy, P., Amling, M., Takeda, S., Priemel, M., Schilling, A.F., Beil, F.T., Shen, J., Karsenty, G., (2000) Cell, 100 (2), pp. 197-207; Stephens, T.W., Basinski, M., Bristow, P.K., Bue-Valleskey, J.M., Burgett, S.G., Craft, L., Hale, J., Heiman, M., (1995) Nature, 377 (6549), pp. 530-532; Erickson, J.C., Hollopeter, G., Palmiter, R.D., (1996) Science, 274 (5293), pp. 1704-1707; Allison, S.J., Baldock, P., Sainsbury, A., Enriquez, R., Lee, N.J., Lin, E.J., Klugmann, M., Gardiner, E.M., (2006) J. Biol. Chem, 281 (33), pp. 23436-23444; Bjurholm, A., Kreicbergs, A., Schultzberg, M., Lerner, U.H., (1992) J. Bone Miner. Res, 7 (9), pp. 1011-1019; Bjurholm, A., Kreicbergs, A., Schultzberg, M., Lerner, U.H., (1998) Acta Physiol. Scand, 134 (3), pp. 451-462; Amano, S., Arai, M., Goto, S., Togari, A., (2007) Biochim. Biophys. Acta, 1770 (6), pp. 966-973; Baldock, P.A., Allison, S.J., Lundberg, P., Lee, N.J., Slack, K., Lin, E.J., Enriquez, R.F., Herzog, H., (2007) J. Biol. Chem, 282 (26), pp. 19092-19102
Keywords: 1 [1 [3 [(3 piperidyl)]]propyl] 2 [[(4 chlorophenoxyl)methyl]indol 3 yl] 2 (4 piperidylpiperidyl)ethan 1 one; 2 [1 (3 chloro 5 isopropoxycarbonylaminophenyl)ethylamino] 6 [2 (5 ethyl 4 methyl 2 thiazolyl)ethyl] 4 morpholinopyridine; 2 [1 (3 chloro 5 isopropyloxycarbonylaminophenyl)ethylamino] 6 [2 (5 ethyl 4 methyl 1,3 thiazol 2 yl)ethyl] 4 morpholinopyridine; Amino Acid Sequence; animal; Animals; bone development; bone mass; bone remodeling; Bone remodelling; bone turnover; Brain; drug antagonism; drug effect; drug potentiation; drug targeting; genetics; gi 264879a; gr 231118; Homeostasis; human; Humans; ligand; Ligands; ly 357897; metabolism; molecular genetics; Molecular Sequence Data; n alpha [3,3 bis(1 naphthyl)propionyl]dextro arginine n [1 benzyl 2 methoxyethyl]amide; n [1 [4 [[[[4 [(dimethylamino)methyl]cyclohexyl]methyl]amino]iminomethyl]benzyl] 2 oxo 2 (1 pyrrolidinyl)ethyl] alpha [(2 naphthalenylsulfonyl)amino]benzenepropanamide; n2 diphenylacetyl n (4 ureidomethylbenzyl)argininamide; nalpha (diphenylacetyl) n (4 hydroxybenzyl) dextro argininamide; neuropeptide Y; neuropeptide Y receptor; neuropeptide Y receptor agonist; neuropeptide Y receptor antagonist; neuropeptide Y [25 dextro arginine]; neuropeptide Y [26 dextro histidine]; neuropeptide Y [31 leucine 34 proline]; neuropeptide Y [6 arginine 34 proline]; neuropeptide Y [7 phenylalanine 34 proline]; neuropeptide Y1 receptor; neuropeptide Y2 receptor; neuropeptide Y4 receptor; neuropeptide Y5 receptor; neuropeptide Y6 receptor; nonhuman; osteoblast; osteoclast; osteolysis; peptide YY; peptide YY [31 leucine 34 proline]; peptide YY [34 proline]; pharmacological blocking; physiology; protein binding; protein expression; protein family; protein isolation; receptor intrinsic activity; Receptors, Neuropeptide Y; review; signal transduction; unclassified drug; Y1 receptor

Osteogenic differentiation of mesenchymal stem cells using PAMAM dendrimers as gene delivery vectors - Santos, J.L.; Oramas, E.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (Journal of Controlled ReleaseJ. Control. Release, 2009)
This paper reports the use of different generations of polyamidoamine (PAMAM) dendrimers for the in vitro transfection of mesenchymal stem cells (MSCs). A systematic study was carried out on the transfection efficiency achieved by the PAMAM dendrimers using a β-galactosidase reporter gene system. Transfection results were shown to be dependent upon the generation of dendrimers, the amine to phosphate group ratio and the cell passage number. In all cases, the transfection efficiency was very low. Nevertheless, it was hypothesized that a low transfection level could be sufficient to promote the in vitro differentiation of MSCs towards the osteoblastic lineage. To address this possibility, dendrimers carrying the human bone morphogenetic protein-2 (hBMP-2) gene-containing plasmid were used. All quantitative (alkaline phosphatase activity, osteocalcin secretion and calcium deposition) and qualitative (von Kossa staining) osteogenic markers were significantly stronger in transfected cells when compared to non-transfected ones. This study not only clearly demonstrates that a low transfection level can be sufficient for inducing in vitro differentiation of MSCs to the osteoblast phenotype but also highlights the importance of focusing research on the development of gene delivery vectors in the concrete application. © 2008 Elsevier B.V. All rights reserved.
Cited By (since 1996): 29Export Date: 21 November 2012Source: ScopusCODEN: JCREEdoi: 10.1016/j.jconrel.2008.11.007PubMed ID: 19070635Language of Original Document: EnglishCorrespondence Address: Tomás, H.; Centro de Química da Madeira, Departamento de Química, Universidade da Madeira, Campus Universitario da Penteada, 9000-390 Funchal, Portugal; email: lenat@uma.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; calcium, 14092-94-5, 7440-70-2; osteocalcin, 136461-80-8; phosphate, 14066-19-4, 14265-44-2; BMP2 protein, human; Bone Morphogenetic Protein 2; Dendrimers; PAMAM Starburst; Polyamines; beta-Galactosidase, 3.2.1.23References: Dai, J., Rabie, A.B.M., Hagg, U., Xu, R.A., Alternative gene therapy strategies for the repair of craniofacial bone defects (2004) Curr. Gene Ther., 4 (4), pp. 469-485;Gersbach, C.A., Phillips, J.E., Garcia, A.J., Genetic engineering for skeletal regenerative medicine (2007) Annu. Rev. Biomed. Eng., 9, pp. 87-119; Kofron, M.D., Laurencin, C.T., Orthopaedic applications of gene therapy (2005) Curr. Gene Ther., 5 (1), pp. 37-61; Kofron, M.D., Laurencin, C.T., Bone tissue engineering by gene delivery (2006) Adv. Drug Deliv. Rev., 58 (4), pp. 555-576; Luo, J., Sun, M.H., Kang, Q., Peng, Y., Jiang, W., Luu, H.H., Luo, Q., He, T.C., Gene therapy for bone regeneration (2005) Curr. Gene Ther., 5 (2), pp. 167-179; Partridge, K.A., Oreffo, R.O., Gene delivery in bone tissue engineering: progress and prospects using viral and nonviral strategies (2004) Tissue Eng., 10 (1-2), pp. 295-307; Turgeman, G., Aslan, H., Gazit, Z., Gazit, D., Cell-mediated gene therapy for bone formation and regeneration (2002) Curr. Opin. Mol. Ther., 4 (4), pp. 390-394; Chen, Y., Cheung, K.M.C., Kung, H.F., Leong, J.C.Y., Lu, W.W., Luk, K.D.K., In vivo new bone formation by direct transfer of adenoviral-mediated bone morphogenetic protein-4 gene (2002) Biochem. Biophys. Res. Commun., 298 (1), pp. 121-127; Lieberman, J.R., Daluiski, A., Stevenson, S., Wu, L., McAllister, P., Lee, Y.P., Kabo, J.M., Witte, O.N., The effect of regional gene therapy with bone morphogenetic protein-2-producing bone-marrow cells on the repair of segmental femoral defects in rats (1999) J. Bone Joint Surg. Am., 81 (7), pp. 905-917; Park, J., Ries, J., Gelse, K., Kloss, F., von der Mark, K., Wiltfang, J., Neukam, F.W., Schneider, H., Bone regeneration in critical size defects by cell-mediated BMP-2 gene transfer: a comparison of adenoviral vectors and liposomes (2003) Gene Ther., 10 (13), pp. 1089-1098; Riew, K.D., Wright, N.M., Cheng, S.L., Avioli, L.V., Lou, J., Induction of bone formation using a recombinant adenoviral vector carrying the human BMP-2 gene in a rabbit spinal fusion model (1998) Calcif. Tissue Int., 63 (4), pp. 357-360; Tsuda, H., Wada, T., Ito, Y., Uchida, H., Dehari, H., Nakamura, K., Sasaki, K., Hamada, H., Efficient BMP2 gene transfer and bone formation of mesenchymal stem cells by a fiber-mutant adenoviral vector (2003) Mol. Ther., 7 (3), pp. 354-365; De Laporte, L., Cruz Rea, J., Shea, L.D., Design of modular non-viral gene therapy vectors (2006) Biomaterials, 27 (7), pp. 947-954; Eliyahu, H., Barenholz, Y., Domb, A.J., Polymers for DNA delivery (2005) Molecules, 10 (1), pp. 34-64; Roth, C.M., Sundaram, S., Engineering synthetic vectors for improved DNA delivery: insights from intracellular pathways (2004) Annu. Rev. Biomed. Eng., 6, pp. 397-426; Corsi, K., Chellat, F., Yahia, L., Fernandes, J.C., Mesenchymal stem cells, MG63 and HEK293 transfection using chitosan-DNA nanoparticles (2003) Biomaterials, 24 (7), pp. 1255-1264; Hamm, A., Krott, N., Breibach, I., Blindt, R., Bosserhoff, A.K., Efficient transfection method for primary cells (2002) Tissue Eng., 8 (2), pp. 235-245; Lakshmipathy, U., Pelacho, B., Sudo, K., Linehan, J.L., Coucouvanis, E., Kaufman, D.S., Verfaillie, C.M., Efficient transfection of embryonic and adult stem cells (2004) Stem Cells, 22 (4), pp. 531-543; Kim, S.W., Ogawa, T., Tabata, Y., Nishimura, I., Efficacy and cytotoxicity of cationic-agent-mediated nonviral gene transfer into osteoblasts (2004) J. Biomed. Mater. Res. A, 71 (2), pp. 308-315; Dufes, C., Uchegbu, I.F., Schatzlein, A.G., Dendrimers in gene delivery (2005) Adv. Drug Deliv. Rev., 57 (15), pp. 2177-2202; Guillot-Nieckowski, M., Eisler, S., Diederich, F., Dendritic vectors for gene transfection (2007) New J. Chem., 31 (7), pp. 1111-1127; Svenson, S., Tomalia, D.A., Dendrimers in biomedical applications-reflections on the field (2005) Adv. Drug Deliv. Rev., 57 (15), pp. 2106-2129; Haensler, J., Szoka, F.C., Polyamidoamine cascade polymers mediate efficient transfection of cells in culture (1993) Bioconjug. Chem., 4 (5), pp. 372-379; Choi, J.S., Nam, K., Park, J., Kim, J.B., Lee, J.K., Park, J., Enhanced transfection efficiency of PAMAM dendrimer by surface modification with l-arginine (2004) J. Control. Release, 99 (3), pp. 445-456; Kono, K., Akiyama, H., Takahashi, T., Takagishi, T., Harada, A., Transfection activity of polyamidoamine dendrimers having hydrophobic amino acid residues in the periphery (2005) Bioconjug. Chem., 16 (1), pp. 208-214; KukowskaLatallo, J.F., Bielinska, A.U., Johnson, J., Spindler, R., Tomalia, D.A., Baker, J.R., Efficient transfer of genetic material into mammalian cells using Starburst polyamidoamine dendrimers (1996) Proc. Natl. Acad. Sci. U. S. A., 93 (10), pp. 4897-4902; Gebhart, C.L., Kabanov, A.V., Evaluation of polyplexes as gene transfer agents (2001) J. Control. Release, 73 (2), pp. 401-416; Aubin, J.E., Osteoprogenitor cell frequency in rat bone marrow stromal populations: role for heterotypic cell-cell interactions in osteoblast differentiation (1999) J. Cell. Biochem., 72 (3), pp. 396-410; Lennon, D.P., Haynesworth, S.E., Young, R.G., Dennis, J.E., Caplan, A.I., A chemically-defined medium supports in-vitro proliferation and maintains the osteochondral potential of rat marrow-derived mesenchymal stem-cells (1995) Exp. Cell Res., 219 (1), pp. 211-222; Bielinska, A.U., Chen, C.L., Johnson, J., Baker, J.R., DNA complexing with polyamidoamine dendrimers: implications for transfection (1999) Bioconjug. Chem., 10 (5), pp. 843-850; Eichman, J.D., Bielinska, A.U., Kukowska-Latallo, J.F., Baker Jr., J.R., The use of PAMAM dendrimers in the efficient transfer of genetic material into cells (2000) Pharm. Sci. Technol. Today, 7, pp. 232-245; Haleem-Smith, H., Derfoul, A., Okafor, C., Tuli, R., Olsen, D., Hall, D.J., Tuan, R.S., Optimization of high-efficiency transfection of adult human mesenchymal stem cells in vitro (2005) Mol. Biotechnol., 30 (1), pp. 9-19; Fischer, D., Li, Y.X., Ahlemeyer, B., Krieglstein, J., Kissel, T., In vitro cytotoxicity testing of polycations: influence of polymer structure on cell viability and hemolysis (2003) Biomaterials, 24 (7), pp. 1121-1131; Jevprasesphant, R., Penny, J., Jalal, R., Attwood, D., McKeown, N.B., D'Emanuele, A., The influence of surface modification on the cytotoxicity of PAMAM dendrimers (2003) Int. J. Pharm., 252 (1-2), pp. 263-266; Wilke, M., Fortunati, E., vandenBroek, M., Hoogeveen, A.T., Scholte, B.J., Efficacy of a peptide-based gene delivery system depends on mitotic activity (1996) Gene Ther., 3 (12), pp. 1133-1142; Xie, Y.B., Yang, S.T., Kniss, D.A., Three-dimensional cell-scaffold constructs promote efficient gene transfection: implications for cell-based gene therapy (2001) Tissue Eng., 7 (5), pp. 585-598; Yamagiwa, H., Endo, N., Tokunaga, K., Hayami, T., Hatano, H., Takahashi, H.E., In vivo bone-forming capacity of human bone marrow-derived stromal cells is stimulated by recombinant human bone morphogenetic protein-2 (2001) J. Bone Miner. Metab., 19 (1), pp. 20-28; Chaudhari, A., Ron, E., Rethman, M.P., Recombinant human bone morphogenetic protein-2 stimulates differentiation in primary cultures of fetal rat calvarial osteoblasts (1997) Mol. Cell. Biochem., 167 (1-2), pp. 31-39; Hay, E., Hott, M., Graulet, A.M., Lomri, A., Marie, P.J., Effects of bone morphogenetic protein-2 on human neonatal calvaria cell differentiation (1999) J. Cell. Biochem., 72 (1), pp. 81-93; Yamaguchi, A., Regulation of differentiation pathway of skeletal mesenchymal cells in cell-lines by transforming growth-factor-beta superfamily (1995) Semin. Cell Biol., 6 (3), pp. 165-173; Yamaguchi, A., Ishizuya, T., Kintou, N., Wada, Y., Katagiri, T., Wozney, J.M., Rosen, V., Yoshiki, S., Effects of BMP-2, BMP-4, and BMP-6 on osteoblastic differentiation of bone marrow-derived stromal cell lines, ST2 and MC3T3-G2/PA6 (1996) Biochem. Biophys. Res. Commun., 220 (2), pp. 366-371; Baltzer, A.W.A., Lattermann, C., Whalen, J.D., Wooley, P., Weiss, K., Grimm, M., Ghivizzani, S.C., Evans, C.H., Genetic enhancement of fracture repair: healing of an experimental segmental defect by adenoviral transfer of the BMP-2 gene (2000) Gene Ther., 7 (9), pp. 734-739; Wang, E.A., Rosen, V., Dalessandro, J.S., Bauduy, M., Cordes, P., Harada, T., Israel, D.I., Wozney, J.M., Recombinant human bone morphogenetic protein induces bone-formation (1990) Proc. Natl. Acad. Sci. U. S. A., 87 (6), pp. 2220-2224; Chuang, C.K., Sung, L.Y., Hwang, S.M., Lo, W.H., Chen, H.C., Hu, Y.C., Baculovirus as a new gene delivery vector for stem cell engineering and bone tissue engineering (2007) Gene Ther., 14 (19), pp. 1417-1424; Aslan, H., Zilberman, Y., Arbeli, V., Sheyn, D., Matan, Y., Liebergall, M., Li, J.Z., Gazit, Z., Nucleofection-based ex vivo nonviral gene delivery to human stem cells as a platform for tissue regeneration (2006) Tissue Eng., 12 (4), pp. 877-889; Noel, D., Gazit, D., Bouquet, C., Apparailly, F., Bony, C., Plence, P., Millet, V., Jorgensen, C., Short-term BMP-2 expression is sufficient for in vivo osteochondral differentiation of mesenchymal stem cells (2003) Stem Cells, 22 (1), pp. 74-85
Keywords: alkaline phosphatase; amine; Amines; animal cell; Animals; article; beta galactosidase; beta-Galactosidase; Bone; Bone morphogenetic protein; bone morphogenetic protein 2; Bone Regeneration; Calcium; Cell culture; cell differentiation; Cell Line; cell lineage; cell survival; Cells; Cells, Cultured; controlled study; dendrimer; Dendrimers; embryo; enzyme activity; Flowcharting; gene expression; Gene transfer; Gene Transfer Techniques; gene vector; Genes, Reporter; genetic transfection; human; human cell; Humans; in vitro study; Kidney; male; Mesenchymal stem cell; Mesenchymal Stem Cells; nonhuman; Nonviral gene delivery; nonviral gene delivery system; Nucleic acids; osteoblast; osteocalcin; Osteogenesis; PAMAM dendrimers; phosphate; plasmid; Plasmids; polyamidoamine; Polyamines; priority journal; protein secretion; Proteins; qualitative analysis; quantitative analysis; rat; Rats; Rats, Wistar; reporter gene; staining

Physical, chemical and in vitro biological profile of chitosan hybrid membrane as a function of organosiloxane concentration - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Costa, M.A.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2009)
We attempted to prepare chitosan-silicate hybrid for use in a medical application and evaluated the physico-chemical properties and osteocompatibility of the hybrids as a function of γ-glycidoxypropyltrimethoxysilane (GPTMS) concentration. Chitosan-silicate hybrids were synthesized using GPTMS as the reagent for cross-linking of the chitosan chains. Fourier transform infrared spectroscopy, 29Si CP-MAS NMR spectroscopy and the ninhydrin assay were used to analyze the structures of the hybrids, and stress-strain curves were recorded to estimate their Young's modulus. The swelling ability, contact angle and cytocompatibility of the hybrids were investigated as a function of the GPTMS concentration. A certain fraction of GPTMS in each hybrid was linked at the epoxy group to the amino group of chitosan, which was associated with the change in the methoxysilane group of GPTMS due to hybridization. The cross-linking density was around 80% regardless of the volume of GPTMS. As the content of GPTMS increased, the water uptake decreased and the hydrophilicity of the hybrids increased except when the content exceeded amolar ratio of 1.5, when it caused a decrease. The values of the mechanical parameters assessed indicated that significant stiffening of the hybrids was obtained by the addition of GPTMS. The adhesion and proliferation of the MG63 osteoblast cells cultured on the chitosan-GPTMS hybrid surface were improved compared to those on the chitosan membrane, regardless of the GPTMS concentration. Moreover, human bone marrow osteoblast cells proliferated on the chitosan-GPTMS hybrid surface and formed a fibrillar extracellular matrix with numerous calcium phosphate globular structures, both in the presence and in the absence of dexamethasone. Therefore, the chitosan-GPTMS hybrids are promising candidates for basic materials that can promote bone regeneration because of their controllable composition (chitosan/GPTMS ratio). © 2008 Acta Materialia Inc.
Cited By (since 1996): 10Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2008.07.022PubMed ID: 18722166Language of Original Document: EnglishCorrespondence Address: Hayakawa, S.; Biomaterial Laboratory, Graduate School of Natural Science and Technology, Okayama University, Tsushima, Okayama-shi, 700-8530, Japan; email: satoshi@cc.okayama-u.ac.jpChemicals/CAS: (3 glycidyloxypropyl)trimethoxysilane, 2530-83-8; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; chitosan, 9012-76-4; silicate, 12627-13-3; Chitosan, 9012-76-4; Cross-Linking Reagents; gamma-glycidoxypropyltrimethoxysilane, 2530-83-8; Silanes; SiloxanesTradenames: AldrichReferences: Lai, J.Y., Lin, F.C., Wang, C.C., Wang, D.M., Effect of nonsolvent additives on the porosity and morphology of asymmetric TPX membranes [J] (1996) J Membrane Sci, 118, pp. 49-61;Wang, D.M., Lin, F.C., Chiang, J.C., Lai, J.Y., Control of porosity of asymmetric TPX membranes [J] (1998) J Membrane Sci, 141, pp. 1-12; Piattelli, A., Scarano, A., Russo, P., Matarasso, S., Evaluation of guided bone regeneration in rabbit tibia using bioresorbable and non-resorbable membranes (1996) Biomaterials, 17 (8), pp. 791-796; Gotfredsen, K., Nimb, L., Hjorting-Hansen, E., Immediate implant placement using a biodegradable barrier, polyhydroxybutyratehydroxyvalerate reinforced with polyglactin 910: an experimental study in dogs (1994) Clin Oral Implants Res, 5 (2), pp. 83-91; Kostopoulos, L., Karring, T., Augmentation of the rat mandible using guided tissue regeneration (1994) Clin Oral Implants Res, 5 (2), pp. 75-82; Kostopoulos, L., Karring, T., Guided bone regeneration in mandibular defects in rats using a bioresorbable polymer (1994) Clin Oral Implants Res, 5 (2), pp. 666-674; Nyman, S., Gottlow, J., Karring, T., The regeneration potential of the periodontal ligament: an experimental study in the monkey (1982) J Clin Periodontal, 9, pp. 257-265; Dupoirieux, L., Pourquier, D., Picot, M.C., Neves, M., Comparative study of three different membranes for guided bone regeneration of rat cranial defects (2001) Int J Oral Maxillofac Surg, 30 (1), pp. 58-62; Zhang, R., Ma, P.X., Porous poly(l-lactic acid)/apatite composites created by biomimetic process (1999) J Biomed Mater Res, 45, pp. 285-293; Murphy, W.L., Kohn, D.H., Mooney, D.J., Growth of continuous bonelike mineral within porous poly(lactide-co-glycolide) scaffolds in vitro (2000) J Biomed Mater Res, 50, pp. 50-58; Lin, F.C., Wang, D.M., Lai, J.Y., Asymmetric TPX membranes. J membranes with high gas flux. (1996) J Membrane Sci, 110, pp. 25-36; Vert, M., Mauduit, J., Li, S., Biodegradation of PLA/GA polymers: increasing complexity (1994) Biomaterials, 15, pp. 1209-1213; Lee, Y.K., Mooney, D.J., Hydrogels for tissue enigineering (2001) Chem Rev, 101, pp. 1869-1879; Domard, A., Rinaudo, M., Preparation and characterization fully deacetylated chitosan (1983) Int J Biol Macromol, 5, pp. 49-52; Chandy, T., Sharma, P.C., Chitosan - as a biomaterial (1990) Biomater Artif Cells Artif Organo, 18, pp. 1-24; Ueno, H., Yamada, H., Tanaka, I., Kaba, N., Matsuura, M., Okumura, M., Accelerating effects of chitosan for healing at early phase of experimental open wound in dogs (1999) Biomaterials, 20, pp. 1407-1414; Muzzareli, R.A.A., Mattioli-Belmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Stimulatory effect on bone formation exerted by a modified chitosan (1994) Biomaterials, 15, pp. 1075-1081; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., In vitro cytocompatibility of MG63 cells on chitosan-organosiloxane hybrid membranes (2005) Biomaterials, 26, pp. 485-493; Prochazkova, S., Varum, K.M., Æstgaard. Quantitative determination of chitosans by ninhydrin (1999) Carbohydr Polym, 38, pp. 115-122; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II: effect of ascorbic acid, β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Coelho, M.J., Cabral, A.T., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part I: osteoblastic differentiation of serially passaged human bone marrow cells cultured in α-MEM and in D-MEM (2000) Biomaterials, 21, pp. 1087-1094; Berridge, V., Tan, A.S., Characterization of the cellular reduction of 3-(4,5-dimethhylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT): subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch Biochem Biophys, 303, pp. 474-482; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Argüelles-Monal, W., Desbriéres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Sol-gel preparation and in vitro deposition of apatite on porous gelatin-siloxane hybrids (2001) J Non Cryst Solid, 285, pp. 116-122; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Novel approach to fabricate porous gelatin-siloxane hybrids for bone tissue engineering (2002) Biomaterials, 23, pp. 4765-4773; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Incorporation of Ca 2+ ions in gelatin-siloxane hybrids through a sol-gel process (2001) J Ceram Soc Jpn, 109, pp. 403-408; Rashidova, S.S.h., Shakarova, D.S.h., Ruzimuradov, O.N., Satabaldieva, D.T., Zalyalieva, S.V., Shpigun, O.A., Bionanocompositional chitosan-silica sorbent for liquid chromatography (2004) J Chromatogr B, 800, pp. 49-53; Hench, L.L., Ethridge, E.C., (1982) Biomaterials an interfacial approach, , Academic Press, New York 10; Xynos, I.D., Hukkanen, M.V.J., Batten, J.J., Buttery, L.D., Hench, L.L., Polak, J.M., Bioglass ® 45S5 stimulates osteoblast turnover and enhances bone formation in vitro: implications and applications for bone tissue engineering (2000) Calcif Tissue Int, 67, pp. 321-329; Xynos, I.D., Edgar, A.J., Buttery, L.D.K., Hench, L.L., Ionic products of bioactive glass dissolution increase proliferation of human osteoblasts and induce insulin-like growth factor II mRNA expression and protein synthesis (2000) Biochem Biophys Res Commun, 276, pp. 461-465; Gough, J.E., Jones, J.R., Hench, L.L., Nodule formation and mineralisation of human primary osteoblasts cultured on a porous bioactive glass scaffold (2004) Biomaterials, 25, pp. 2039-2046; Maniatopoulos, C., Sodek, J., Melcher, A., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Fernandes, M.H., Costa, M.A., Carvalho, G.S., Mineralization in serially passaged human alveolar bone cells (1997) J Mater Sci Mater Med, 8, pp. 61-65; Costa, M.A., Gutierres, M., Almeida, L., Lopes, M.A., Santos, J.D., Fernandes, M.H., In vitro mineralization of human bone marrow cells cultured on Bonelike ® (2004) Key Eng Mater, 254-256, pp. 821-824
Keywords: (3 glycidyloxypropyl)trimethoxysilane; article; assay; Biocompatibility; Bone Marrow Cells; calcium phosphate; cell adhesion; Cell Line, Tumor; cell proliferation; cell survival; cell viability; Chemical analysis; chitosan; concentration (parameters); controlled study; cross linking; Cross-Linking Reagents; extracellular matrix; human; human cell; Humans; hydrophobicity; in vitro study; infrared spectroscopy; Magnetic Resonance Spectroscopy; Microscopy, Electron, Scanning; molecular hybridization; Nuclear magnetic resonance spectroscopy; Organic-inorganic hybrid; osteoblast; Osteoblasts; Osteocompatibility; physical chemistry; priority journal; Silanes; silicate; siloxane; Siloxanes; Spectrophotometry, Ultraviolet; Spectroscopy, Fourier Transform Infrared; stress strain relationship; structure analysis; surface property; Tissue engineering; unclassified drug; water transport; γ-Glycidoxypropyltrimethoxysilane (GPTMS)

Prediction of neonatal acidemia by computer analysis of fetal heart rate and ST event signals - Costa, A.; Ayres-de-Campos, D.; Costa, F.; Santos, C.; Bernardes, J. (American Journal of Obstetrics and GynecologyAm. J. Obstet. Gynecol., 2009)
Objective: The objective of the study was to evaluate the accuracy of computer analysis of fetal heart rate (FHR) and ST event signals in prediction of neonatal acidemia. Study Design: One hundred forty-eight FHR tracings were evaluated to identify red alerts provided by the system, based on automated analysis of FHR and ST event signals, and compared with the occurrence of umbilical artery acidemia (pH ≤7.05). Results: The presence of red alerts obtained sensitivity of 1.00 (95% confidence interval [CI], 0.56-1.00), specificity of 0.94 (95% CI, 0.89-0.97), positive predictive value (PPV) of 0.47 (95% CI, 0.22-0.72), negative predictive value (NPV) of 1 (95% CI, 0.96-1.00), positive likelihood ratio (PLR) of 17.6 (95% CI, 9.0-34.5), and negative likelihood ratio (NLR) of 0. When limiting analysis to red alerts that did not include ST data, sensitivity was 0.57 (95% CI, 0.20-0.88), specificity was 0.97 (95% CI, 0.92-0.99), PPV was 0.50 (95% CI, 0.17-0.82), NPV was 0.98 (95% CI, 0.93-0.99), PLR was 20.14 (95% CI, 6.3-64.2), and NLR was 0.44 (95% CI, 0.19-1.04). Conclusion: Computer analysis of FHR and ST event signals provide higher accuracy in predicting neonatal academia. © 2009 Mosby, Inc. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: AJOGAdoi: 10.1016/j.ajog.2009.04.033PubMed ID: 19539895Language of Original Document: EnglishCorrespondence Address: Costa, A.; Departamento de Ginecologia e Obstetrícia, Faculdade de Medicina, Hospital S. JoãoPortugal; email: cosantonia@gmail.comReferences: (2006) Perinatal Mortality Surveillance 2004: England, Wales, and Northern Ireland, , CEMACH (Confidential Enquiry into Maternal and Child Health), Confidential Enquiry into Maternal and Child Health, London, UK;(1997) 4th annual report, , CESDI (Confidential Enquiry into Stillbirths and Deaths in Infancy), Maternal and Child Health Research Consortium, London, UK; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310; Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-165; Bernardes, J., Costa-Pereira, A., Ayres-de-Campos, D., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57, pp. 33-37; Donker, D.K., van Geijn, H.P., Hasman, A., Interobserver variation in the assessment of fetal heart rate recordings (1993) Eur J Obstet Gynecol Reprod Biol, 52, pp. 21-28; Neilson, J.P., Fetal electrocardiogram (ECG) for fetal monitoring during labour (2006) Cochrane Database Syst Rev, 3; Doria, V., Papageorghiou, A., Gustafsson, A., Ugwumadu, A., Farrer, K., Arulkumaran, S., Review of the first 1502 cases of ECG-ST waveform analysis during labour in a teaching hospital (2007) BJOG, 114, pp. 1202-1207; Westerhuis, M., Kwee, A., van Ginkel, A., Drogtrop, A., Gyselaers, W., Visser, G., Limitations of ST analysis in clinical practice: three cases of intrapartum metabolic acidosis (2007) BJOG, 114, pp. 1194-1201; Amer-Wahlin, I., Arulkumaran, S., Hagberg, H., Marsal, K., Visser, G., Fetal electrocardiogram: ST waveform analysis in intrapartum surveillance (2007) BJOG, 114, pp. 1191-1193; Dawes, G.S., Redman, C.W., Smith, J.H., Improvements in the registration and analysis of fetal heart rate records at the bedside (1985) Br J Obstet Gynaecol, 92, pp. 317-325; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: the antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118, pp. 52-60. , SisPorto Multicentre Validation Study Group; Dawes, G.S., Moulden, M., Redman, C.W.G., System 8000: computerized antenatal FHR analysis (1991) J Perinat Med, 19, pp. 47-51; Bernardes, J., Moura, C., Marques-de-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sá, J.P., Pereira-Leite, L., SisPorto 2.0-a program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Ayres-de-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto® 3.5-a central fetal monitoring station with online alerts based on computerized cardiotocogram+S.T.event analysis (2008) J Perinat Med, 36, pp. 260-264; Ayres-de-Campos, D., Bernardes, J., Kwee, A., Westehuis, M., Visser, G.H.A., Computer quantification of short-term variability as an adjunct to fetal electrocardiographic monitoring (2007) BJOG, 114, pp. 1446-1447; Downing, J.W., Houlton, P.C., Barclay, A., Extradural analgesia for cesarean section: a comparison with general anesthesia (1979) Br J Anaesth, 51, pp. 367-374; Crawford, J.S., James, F.M., Davies, P., Crawley, M., A further study of general anaesthesia for cesarean section (1976) Br J Anaesth, 48, pp. 661-667; Huch, A., Huch, C., Rooth, G., Guidelines for blood sampling and measurement of pH and blood gas values in obstetrics (1994) Eur J Obstet Gynecol Reprod Biol, 54, pp. 165-175; ACOG technical bulletin. Umbilical artery blood acid-base analysis (1996) Int J Gynecol Obstet, 52, pp. 305-310; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: a time for quality data (1994) Br J Obstet Gynaecol, 101, pp. 1054-1063; Low, J.A., Intrapartum fetal asphyxia: definition, diagnosis and classification (1997) Am J Obstet Gynecol, 176, pp. 957-959; Fleiss, J.L., (1981) Statistical methods for rates and proportions. 2nd ed., , John Wiley & Sons, New York, NY Section 5.6; Keith, R.D., Beckley, S., Garibaldi, J.M., Westgate, J.A., Ifeachor, E.C., Greene, K.R., A multicentre comparative study of 17 experts and an intelligent computer system for managing labour using cardiotocogram (1995) Br J Obstet Gynecol, 102, pp. 668-700; Chung, T.K., Mohajer, M.P., Yang, Z.j., Chang, A.M., Sahota, D.S., The prediction of fetal acidosis at birth by computerised analysis of intrapartum cardiotocography (1995) Br J Obstet Gynaecol, 102, pp. 454-460; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., Computer assessment of the intrapartum cardiotocogram. II. The value of computer assessment compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464; Policy statement. The Apgar score-American Academy of Pediatrics and American College of Obstetricians and Gynecologists (2006) Pediatrics, 117, pp. 1444-1447; Casey, B.M., McIntire, D.D., Leveno, K.J., The continuing value of the Apgar score for the assessment of the newborn infants (2001) N Engl J Med, 334, pp. 467-471; Moster, D., Lie, R.T., Irgens, L.M., Bjerkedal, T., Markestad, The association of Apgar score with subsequent death and cerebral palsy: a population-based study in term infants (2001) J Pediatr, 138, pp. 798-803
Keywords: acidemia; Acidosis; article; autoanalysis; Cardiotocography; computer analysis; computer assisted; computer prediction; Diagnosis, Computer-Assisted; diagnostic value; Electrocardiography; Female; Fetal heart rate; Fetal hypoxia; Fetal monitoring; fetus electrocardiography; fetus heart rate; Heart Rate, Fetal; human; Humans; Infant, Newborn; major clinical study; male; newborn; newborn acidosis; observational study; pH; Predictive Value of Tests; priority journal; Prospective Studies; prospective study; Reproducibility of Results; sensitivity and specificity; signal transduction; ST segment; umbilical artery

Skin adhesive versus subcuticular suture for perineal skin repair after episiotomy - A randomized controlled trial - Mota, R.; Costa, F.; Amaral, A.; Oliveira, F.; Santos, C.C.; Ayres-de-Campos, D. (Acta Obstetricia et Gynecologica ScandinavicaActa Obstet. Gynecol. Scand., 2009)
Objective. Surgical repair of perineal lesions after delivery is frequently associated with pain and discomfort, interfering with the normal activities of the puerperium. The aim of this study was to compare perineal skin repair after episiotomy with adhesive glue versus a subcuticular suture, regarding the incidence of pain and wound complications. Study design. Randomized clinical trial. Setting. Tertiary care university hospital. Material and methods. One hundred women having mediolateral episiotomy at vaginal delivery were enrolled. They were randomized to receive skin adhesive (n = 53) or subcuticular suture (n = 47) for closure of perineal skin. The main outcome measure was self-evaluated pain in the 30 days following delivery. Secondary outcome measures were technical difficulties reported with the procedure, duration of surgical repair, wound complications observed at 42-68 hours post-partum and re-initiation of sexual activity by 30 days post-partum. Results. No significant differences were observed between the two groups in incidence of technical difficulties and failed procedures, pain during the procedure, wound complications at hospital discharge, self-evaluated measures of pain at 7 and 30 days or re-initiation of sexual activity by 30 days post-partum. The skin adhesive group had a significantly shorter mean duration of the procedure (four minutes less). Conclusion. Perineal skin closure using adhesive glue is faster than subcuticular suture, and associated with a similar incidence of complications and pain in the first 30 days.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: AOGSAdoi: 10.1080/00016340902883133Language of Original Document: EnglishCorrespondence Address: Mota, R.; Serviço de Ginecologia e Obstetrícia, Hospital de S. João, 4200-319 Porto, Portugal; email: sisporto@med.up.ptChemicals/CAS: Tissue Adhesives; cyanoacrylic acid octyl ester, 6701-17-3; polyglactin, 26780-50-7, 34346-01-5Tradenames: Dermabond, EthiconManufacturers: EthiconReferences: Kettle, C., Hills, R.K., Jones, P., Darby, L., Gray, R., Johanson, R., Continuous versus interrupted perineal repair with standard or rapidly absorbed sutures after spontaneous vaginal birth: A randomized controlled trial (2002) Lancet, 359, pp. 2217-2223;Gordon, B., Mackrodt, C., Fern, E., Truesdale, A., Ayers, S., Grant, A., The Ipswich Childbirth Study: 1. A randomized evaluation of two stage postpartum perineal repair leaving the skin unsutured (1998) Br J Obstet Gynaecol, 105, pp. 435-440; Mackrodt, C., Gordon, B., Fern, E., Ayers, S., Truesdale, A., Grant, A., The Ipswich Childbirth Study: 2. A randomized comparison of polyglactin 910 with chromic catgut for postpartum perineal repair (1998) Br J Obstet Gynaecol, 105, pp. 441-445; Kettle, C., Johanson, R.B., Continuous versus interrupted sutures for perineal repair (2000) Cochrane DataBase Syst Rev, (2). , CD000947; Kettle, C., Hills, R.K., Ismail, K.M.K., Continuous versus interrupted sutures for repair of episiotomy or second degree tears (2007) Cochrane DataBase Syst Rev, (4). , CD000947; Gemynthe, A., Langhoff-Roos, J., Sahl, S., Knudsen, J., New VICRYL formulation: An improved method of perineal repair? (1996) Br J Midwifery, 4, pp. 230-234; Oboro, V.O., Tabowei, T.O., Loto, O.M., Bosah, J.O., A multicentre evaluation of the two-layered repair of postpartum perineal trauma (2003) J Obstet Gynaecol, 23, pp. 5-8; Kindberg, S., Stehouwer, M., Hvidman, L., Henriksen, T.B., Postpartum perineal repair performed by midwives: A randomised trial comparing two suture techniques leaving the skin unsutured (2008) Br J Obstet Gynaecol, 115, pp. 472-479; Gennari, R., Rotmensz, N., Ballardini, B., Scevola, S., Perego, E., Zanini, V., A prospective, randomized, controlled clinical trial of tissue adhesive (2-octylcyanoacrylate) versus standard wound closure in breast surgery (2004) Surgery, 136, pp. 593-599; Bernard, L., Doyle, J., Friedlander, S.F., Eichenfield, L.F., Gibbs, N.F., Cunningham, B.B., A prospective comparison of octylcya-noacrylate tissue adhesive (dermabond) and suture for the closure of excisional wounds in children and adolescents (2001) Arch Dermatol, 137, pp. 1177-1180; Matin, S.F., Prospective randomized trial of skin adhesive versus sutures for closure of 217 laparoscopic port-site incisions (2003) J Am Coll Surg, 196, pp. 845-853; Bhende, S., Rothenburger, S., Spangler, D.J., Dito, M., In vitro assessment of microbial barrier properties of Dermabond( topical skin adhesive (2002) Surg Infect, 3, pp. 251-257; Rogerson, L., Mason, G.C., Roberts, A.C., Preliminary experience with twenty perineal repairs using Indermil tissue adhesive (2000) Eur J Obstet Gynecol Reprod Biol, 88, pp. 139-142; Bowen, M.L., Selinger, M., Episiotomy closure comparing enbucrilate tissue adhesive with conventional sutures (2002) Int J Gynecol Obstet, 78, pp. 201-205; Adoni, A., Anteby, E., The use of Histoacryl for the episiotomy repair (1991) Br J Obstet Gynaecol, 98, pp. 476-478; Man, J., Quinn, J., Cyanoacrylate tissue adhesives (1997) Am J Cosm Surg, 14, pp. 413-416; Maw, J.L., Quinn, J.V., Wells, G.A., Ducic, Y., Odell, P.F., Lamothe, A., A prospective comparison of octylcyanoacrylate tissue adhesive and suture for the closure of head and neck incisions (1997) J Otolaryngol, 26, pp. 26-30
Keywords: adult; article; clinical trial; comparative study; controlled clinical trial; controlled study; cyanoacrylic acid octyl ester; edema; episiotomy; Episiotomy closure; Female; granuloma; human; Humans; injury; major clinical study; obstetric care; pain; pain assessment; Perineal repair; perineum; perineum injury; polyglactin; priority journal; questionnaire; randomized controlled trial; sexual intercourse; Skin; Skin adhesive; suture; Suture Techniques; suturing method; Tissue adhesive; Tissue Adhesives; treatment outcome; vaginal delivery; wound closure; wound dehiscence; Wounds and Injuries

3-D biomodelling technology for maxillofacial reconstruction - Oliveira, M.; Sooraj Hussain, N.; Dias, A.G.; Lopes, M.A.; Azevedo, L.; Zenha, H.; Costa, H.; Santos, J.D. (Materials Science and Engineering CMater. Sci. Eng. C, 2008)
Biomodel is a product of rapid prototyping process that represents a new approach for surgical planning and simulation. Biomodels were found to be particularly effective to locate an exact defect with good measurement accuracy and without any risk to the patients' health. These models could provide surgeons a realistic impression of complex structures before surgical intervention, allowing a define diagnosis and a precise preoperative simulation of skeleton modifying interventions. This work reports on the application of innovative 3-D biomodelling technology in the maxillofacial reconstruction. This technology allows for the calculation of the exact contours, angulations, length and general morphology of iliac crest and fibula flaps for maxillofacial reconstruction in a total of 28 clinical cases. Clinical results have shown that by using this technique, much better facial symmetry and improved functionality were achieved after surgery, which resulted in enormous benefits for treated patients. © 2008 Elsevier B.V. All rights reserved.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.msec.2008.02.007Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Instituto de Engenharia Biomédica (INEB), Laboratório de Biomateriais, Rua Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Pessa, J.E., (2001) Am. J. Orthod. Dentofac. Orthop., 119, p. 117;Poukens, J., Haex, J., Riediger, D., (2003) Comput. Aided Surg., 8 (3), p. 146; Brown, G.A., Milner, B., Firoozbakhsh, K., (2002) J. Orthop. Trauma, 16 (5), p. 347; Berry, E., Brown, J.M., Connell, M., Craven, C.M., Efford, N.D., Radjenovic, A., Smith, M.A., (1997) Med. Eng. Phys., 19 (1), p. 90; Urso, P.S.D., Barker, T.M., Earwaker, W.J., Bruce, L.J., Atkinson, R.L., Lanigan, M.W., Arvier, J.F., Effeney, D.J., (1999) J. Cranio-Maxillo-Facial Surg., 27, p. 30; Urso, P.S.D., Thompson, R.G., (1998) Aust. N.Z. J. Obstet. Gynaecol., 38, p. 205; Clair, J.J., (1996) J. Mater. Process. Technol., 57, p. 393; Pham, D.T., Gault, R.S., (1998) Int. J. Mach. Tools Manuf., 38, p. 1257; Onuh, S.O., Hon, K.K.B., (1998) Int. J. Mach. Tools Manuf., 38, p. 329; Barker, T.M., Earwaker, W.J., Lisle, D.A., (1994) Australas. Radiol., 38, p. 106; Peckitt, N.S., (1999) Br. J. Oral Maxillofac. Surg., 37, p. 353; Holck, D.E.E., Boyd Jr., E.M., Ng, J., Mauffray, R.O., B, (1999) Ophthalmology, 106, p. 1214; Pessa, J.E., Desvigne, L.D., Lambros, V.S., Nimerick, J., Sugunan, B., Zadoo, V.P., (1999) Aesthet. Plast. Surg., 23, p. 337; Gutierres, M., Dias, A.G., Lopes, M.A., Sooraj Hussain, N., Cabral, A.T., Almeida, L., Santos, J.D., (2007) J. Mater. Sci. Mater. Med., 18, p. 2377; Gauthier, O., Bouler, J.M., Aguado, E., Pilet, P., Daculsi, G., (1998) Biomaterials, 19 (1-3), p. 133; Lu, J.X., Flautre, B., Anselme, K., Hardouin, P., Gallur, A., Descamps, M., Thierry, B., (1999) J. Mater. Sci., Mater. Med., 10 (2), p. 111; Martina, M., Subramanyam, G., Weaver, J.C., Hutmacher, D.W., Morse, D.E., Valiyaveettil, S., (2005) Biomaterials, 26 (28), p. 5609; Moroni, L., de Wijn, J.R., van Blitterswijk, C.A., (2006) Biomaterials, 27 (7), p. 974; Sanghera, B., Naique, S., Papaharilaou, Y., Amis, A., (2001) Rapid Prototyping J., 7 (5), p. 275; Pentecost, J.O., Icardo, J., Thornburg, K.L., (1999) Comput. Med. Imaging Graph., 23, p. 45; Urso, P.S.D., Atkinson, R.L., Lanigan, M.W., Earwaker, W.J., Bruce, L.J., Holmes, A., Barker, T.M., Thompson, RG., (1998) Br. J. Plast. Surg., 51, p. 522
Keywords: 3D Biomodelling; Biomodels; Complex structures; Concurrent engineering; Facial symmetries; Free flap designing; Health risks; Job analysis; Maxillofacial reconstruction; Measurement accuracies; New approaches; Process engineering; Prototyping processes; Rapid prototyping; Repair; Restoration; Surgical interventions; Surgical planning; Three dimensional

Biocompatibility evaluation of DLC-coated Si 3N 4 substrates for biomedical applications - Salgueiredo, E.; Vila, M.; Silva, M.A.; Lopes, M.A.; Santos, J.D.; Costa, F.M.; Silva, R.F.; Gomes, P.S.; Fernandes, M.H. (Diamond and Related MaterialsDiamond Relat. Mat., 2008)
DLC coatings are of enormous interest for biotribological applications due to their biocompatibility, auto-lubricious, and non-stick properties. The most demanding implant is the hip joint. Alternative materials to metal alloys are being increasingly investigated aiming low wear debris volume, in any case innocuous wear particles. Silicon nitride (Si 3N 4) ceramics are light, tough, mechanical resistant, inert materials, turning them suitable for high-load medical applications. In this study, Si 3N 4 polished substrates were coated with adherent DLC coatings grown by DC magnetron sputtering to reduce of the friction forces against any antagonist material. Surface characterization results showed that the developed material is quite hydrophobic, with a total surface tension of 45.7 mN/m (polar component: 9.1 mN/m; dispersive component: 36.6 mN/m), and a zeta potential of - 35.0 ± 1.3 mV. In vitro testing using an acellular simulated body fluid (SBF) showed no apatite layer formation ability, as confirmed by SEM observation and analysis of the solution ions concentration with immersion time. MG63 osteoblast-like cells showed poor adhesion on the DLC films but the adherent cells displayed a normal morphology and, as compared to standard polystyrene tissue culture plates, exhibited a higher cell growth rate, suggesting no indication of cytotoxicity. Results suggested that the novel DLC-coated Si 3N 4 biomaterial should be adequate to be used for articular prostheses medical application. © 2007 Elsevier B.V. All rights reserved.
Cited By (since 1996): 30Export Date: 21 November 2012Source: ScopusCODEN: DRMTEdoi: 10.1016/j.diamond.2007.08.019Language of Original Document: EnglishCorrespondence Address: Silva, R.F.; CICECO, Glass and Ceramics Eng. Department, University of Aveiro, 3810-193 Aveiro, Portugal; email: rsilva@cv.ua.ptReferences: Sargeant, A., Goswami, T., (2006) Mater. Des., 27, p. 287;Petzow, G., Herrmann, M., (2002) Structure and Bonding, 102, p. 47. , Janson M. (Ed), Springer-Verlag, Berlin; Narayan, R.J., (2005) Mater. Sci. Eng., C, Biomin. Mater., Sens. Syst., 25, p. 405; Cui, F.Z., Li, D.J., (2000) Surf. Coat. Technol., 131, p. 481; Zhao, Q., Liu, Y., Abel, E.W., (2004) J. Colloid Interface Sci., 280, p. 174; Vila, M., Abreu, C.S., Salgueiredo, E., Almeida, F.A., Fernandes, A.J.S., Costa, F.M., Gomes, J.R., Silva, R.F., (2006) Thin Solid Films, 515, p. 2192; Fairbrother, F., Mastin, H., (1924) J. Chem. Soc., 75, p. 2318; Owens, D.K., Wendt, R.D., (1969) J. Appl. Polym. Sci., 13, p. 1741; Kokubo, T., Takadama, H., (2006) Biomaterials, 27, p. 2907; Strom, G., Fredriksson, M., Stenius, P., (1987) J. Colloid Interface Sci., 119, p. 352; Schulz, H., Leonhardt, M., Scheibe, H.J., Schultrich, B., (2005) Surf. Coat. Technol., 200, p. 1123; Wilson, C.J., (2005) Tissue Eng., 11, p. 1; Haynes, C.A., Norde, W., (1994) Colloids Surf., B Biointerfaces, 2, p. 517; Shelton, R.M., Rasmussen, A.C., Davies, J.E., (1988) Biomaterials, 9, p. 24; Davies, J.E., Causton, B., Bovell, Y., Davy, K., Sturt, C.S., (1986) Biomaterials, 7, p. 231; Dearnaley, G., Arps, J.H., (2005) Surf. Coat. Technol., 200, p. 2518
Keywords: Biocompatibility; Biomedical applications; Cell cultures; Coatings; Diamond like carbon films; DLC coatings; Hip joint; hydrophobicity; Magnetron sputtering; Medical applications; Metal alloys; Simulated body fluid (SBF); Tribology; Wear of materials

Biodegradable chitosan-silicate porous hybrids for drug delivery - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A. (Key Engineering MaterialsKey Eng Mat, 2008)
Porous chitosan-silicate hybrids were prepared by freeze-drying the precursor sol solutions synthesized from chitosan and 3- glycidoxypropyltrimethoxysilane (GPTMS). Degradability of and the release of cytochrome C in to phosphate buffer saline solution (PBS) were examined as a function of the GPTMS content. The hybrids were less degradable with larger GPTMS contents, and the cytochrome C release profile was so controllable as to give either burst release or slow one due to the GPTMS content. Thus, the present porous chitosan-silicate hybrids were considered applicable to drug delivery systems.
Keywords: biodegradability; Buffer saline solution; chitosan; Chitosan silicate hybrid; Chitosan-silicate hybrid; Drug delivery; Porous materials; Proteins; Silicates; Synthesis (chemical)

Bone ingrowth in macroporous Bonelike ® for orthopaedic applications - Gutierres, M.; Lopes, M.A.; Sooraj Hussain, N.; Lemos, A.F.; Ferreira, J.M.F.; Afonso, A.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Acta BiomaterialiaActa Biomater., 2008)
The aim of this study was to evaluate the biological behaviour of porous scaffold structures of Bonelike ® which is suitable for either direct clinical use or tissue engineering applications. Porous cylindrical specimens 8 × 10 mm were implanted in the lateral aspect of the tibia of 13 patients (mean age 54 years), during osteotomy surgery for the treatment of medial compartment osteoarthritis of the knee. Implanted cylinders were retrieved at the same time as the removal of the blade plates at 3, 6, 9 and 12 months. Scanning electron microscopy and histological evaluations were performed to observe the biological responses of human bone tissue to porous Bonelike ®. The penetration depth was determined for all implantation periods, and after 6 months it was already possible to see new bone in the centre of the implanted cylinders, which gives 100% of penetration depth for all implantations periods except for 3 months when bone could only be seen in the peripherical region. Regarding the percentage of the area covered by new bone calculated from two-dimensional histological sections, values of 53 ± 15, 76 ± 12 and 88 ± 9% were achieved for 6, 9 and 12 months, respectively. Due to its structural features porous Bonelike ® permitted effective vascularization and bone ingrowth, and therefore was fully osteointegrated as shown in the histological surveys. A slow biomaterial degradation with implantation time is envisaged since the material has displayed surface degradation. Bonelike ® scaffolds show potential for complete ingrowth of osseous tissue and restoration of vascularization throughout the defected site. © 2007.
Cited By (since 1996): 13Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2007.06.009PubMed ID: 17716960Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; FEUP - Faculdade de Engenharia, Universidade do Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Bone SubstitutesTradenames: BonelikeReferences: Akamatsu, Y., Koshino, T., Saito, T., Wada, J., Changes in osteosclerosis of the osteoarthritic knee after high tibial osteotomy (1997) Clin Orthop, 334, pp. 207-214;Coventry, M.B., Ilstrup, D.M., Wallrichs, S.L., Proximal tibial osteotomy. A critical long-term study of eighty-seven cases (1993) J Bone Joint Surg, 75 -A, pp. 196-201; Hernigou, P., Medevielle, D., Debeyre, J., Goutallier, D., Proximal tibial osteotomy for osteoarthritis with varus deformity. A ten to thirteen-year follow-up study (1987) J Bone Joint Surg Am, 69, pp. 332-354; Hernigou, P., Ma, W., Open wedge tibial osteotomy with acrylic bone cement as bone substitute (2001) Knee, 8, pp. 103-110; Koshino, T., Murase, T., Saito, T., Medial opening-wedge high tibial osteotomy with use of porous hydroxyapatite to treat medial compartment osteoarthritis of the knee (2003) J Bone Joint Surg Am, 85, pp. 78-85; Simske SJ, Ayers RA, Bateman TA. Porous Materials for Bone Engineered. In: Materials Science Forum. Zurich: Trans Tech Publications; 1997. Vol. 250, pp. 151-182Hing, K.A., Bone repair in the twenty-first century: biology, chemistry or engineering? (2004) Philos Trans A Math Phys Eng Sci, 362 (1825), pp. 2821-2850; Hui, P.W., Leung, P.C., Sher, A., Fluid conductance of cancellous bone graft as a predictor for graft-host interface healing (1996) J Biomech, 29 (1), pp. 123-132; Ben-Nissan, B., Natural bioceramics: from coral to bone and beyond (2003) Curr Opin Solid State Mater Sci, 7 (4-5), p. 283; Shors, E.C., Holmes, R.E., Porous hydroxyapatite (1993) Introduction to Biomaterials, pp. 181-198. , Hench L.L., and Wilson J. (Eds), World Scientific, Singapore; Prado da Silva, M.H., Lemos, A.F., Gibson, I.R., Ferreira, J.M.F., Santos, J.D., Porous glass reinforced hydroxyapatite materials produced with different organic additives (2002) J Non-Cryst Solids, 304, pp. 286-292; Prado da Silva, M.H., Lemos, A.F., Ferreira, J.M.F., Lopes, M.A., Santos, J.D., Production of porous biomaterials based on glass reinforced hydroxyapatite composites (2002) Key Eng Mater, 230-232, pp. 483-486; Rocha, J., Lemos, A., Agathopoulos, S., Valério, P., Kannan, S., Oktar, F., Scaffolds for bone restoration from cuttlefish (2005) Bone, 37 (6), pp. 850-857; Sepulveda, P., Binner, J.G.P., Processing of cellular ceramics by foaming and in situ polymerization of organic monomers (1999) J Eur Ceram Soc, 19 (12), pp. 2059-2066; Ozgur Engin, N., Cuneyt Tas, A., Manufacture of macroporous calcium hydroxyapatite bioceramics (1999) J Eur Ceram Soc, 19 (13-14), pp. 2569-2572; Peng, H.X., Fan, Z., Evans, J.R.G., Busfield, J.J.C., Microstructure of ceramic foams (2000) J Eur Ceram Soc, 20 (7), pp. 807-813; Komlev Vladimir, S., Barinov Serguei, M., Koplik Elena, V., A method to fabricate porous spherical hydroxyapatite granules intended for time-controlled drug release (2002) Biomaterials, 23 (16), pp. 3449-3454; Milosevski, M., Bossert, J., Milosevski, D., Gruevska, N., Preparation and properties of dense and porous calcium phosphate (1999) Ceram Int, 25, pp. 693-696; Tadic, D., Beckmann, F., Schwarz, K., Epple, M., A novel method to produce hydroxyapatite objects with interconnecting porosity that avoids sintering (2004) Biomaterials, 25, pp. 3335-3340; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., Influence of characteristics of the starting hydroxyapatite powders and of deagglomeration procedure, on rheological behaviour of the suspensions (2004) Mater Sci Forum, 455-456, pp. 361-365; Lemos, A.F., Ferreira, J.M.F., Porous bioactive calcium carbonate implants processed by starch consolidation (2000) J Mat Sci Eng C, C11, pp. 35-40; Lemos, A.F., Ferreira, J.M.F., Combining foaming and starch consolidation methods to develop macroporous HA implants (2004) Key Eng Mater, 254-256, pp. 1041-1044; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., New method for the incorporation of soluble bioactive glasses to reinforce porous HA structures (2004) Key Eng Mater, 254-256, pp. 1033-1036; Gauthiera, O., Boulerb, J.M., Aguadoa, E., Piletb, P., Daculsi, G., Macroporous biphasic calcium phosphate ceramics: influence of macropore diameter and macroporosity percentage on bone ingrowth (1998) Biomaterials, 19, pp. 133-139; Hing, A.K., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Mediation of bone ingrowth in porous hydroxyapatite bone graft substitutes (2004) J Biomed Mater Res, 68 A, pp. 187-200; Rubin, P.A., Popham, J.K., Bilyk, J.R., Shore, J.W., Comparison of fibrovascular ingrowth into hydroxyapatite and porous polyethylene orbital implants (1994) Ophthal Plast Reconstr Surg, 10 (2), pp. 96-103; Hing, K.A., Annaz, B., Saeed, S., Revell, P.A., Buckland, T., Microporosity enhances bioactivity of synthetic bone graft substitutes (2005) J Mater Sci: Mater Med, 16, pp. 467-475; Klawitter, J.J., Bagwell, J.G., Weinstein, A.M., Sauer, B.W., An evaluation of bone growth into porous high density polyethylene (1976) J Biomed Mater Res, 10 (2), pp. 311-323; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Quantification of bone ingrowth within bone-derived porous hydroxyapatite implants of varying density (1999) J Mater Sci: Mater Med, 10, pp. 663-670; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Biomechanical assessment of bone ingrowth in porous hydroxyapatite (1997) J Mater Sci: Mater Med, 8, pp. 731-736; Ayers, R.A., Wolford, L.M., Bateman, T.A., Ferguson, V.L., Simske, S.J., Quantification of bone ingrowth into porous block hydroxyapatite in humans (1999) J Biomed Mater Res, 47, pp. 54-59; Lu, J.X., Flautre, B., Anselme, K., Hardouin, P., Gallur, A., Descamps, M., Role of interconnections in porous bioceramics on bone recolonization in vitro and in vivo (1999) J Mater Sci: Mater Med, 10 (2), pp. 111-120; Eggli, P.S., Muller, W., Schenk, R.K., Porous hydroxyapatite and tricalcium phosphate cylinders with two different pore size ranges implanted in the cancellous bone of rabbits - A comparative histomorphometric and histologic study of bony ingrowth and implant substitution (1988) Clin Orthop Relat Res, 232, pp. 127-138; Kuhne, J.H., Bartl, R., Frisch, B., Hammer, C., Jansson, V., Zimmer, M., Bone formation in coralline hydroxyapatite. Effects of pore size studied in rabbits (1994) Acta Orthop Scand, 65 (3), pp. 246-252; Holmes, R., Mooney, V., Bucholz, R., Tencer, A., A coralline hydroxyapatite bone graft substitute. Preliminary report (1984) Clin Orthop Relat Res, 188, pp. 252-262; Lopes, M.A., Knowles, J.C., Santos, J.D., Structural insights of glass-reinforced hydroxyapatite composites by Rietveld refinement (2000) Biomaterials, 21 (18), pp. 1905-1910; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass-reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39 (2), pp. 244-251; Santos JD, Hastings G, Knowles JC. Sintered hydroxyapatite compositions and method for the preparation thereof. Worldwide Application (PCT), Patent No. 1 189 851, 1999Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: fracture toughness and hardness dependence on microstructural characteristics (1999) Biomaterials, 20 (21), pp. 2085-2090; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: Secondary phase proportions and densification effects on biaxial bending strength (1999) J Biomed Mater Res, 48 (5), pp. 734-740; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, Surface tension and Zeta potential measurements of glass reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Direct and Indirect effects of P 2O 5 - glass reinforced - hydroxyapatite composites and growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibiae of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., HA and Double layer HA-P 2O 5/CaO Glass coatings: influence of chemical composition on human bone marrow cells osteoblastic behaviour (2001) J Mater Sci: Mater Med, 12, pp. 629-638; Gutierres, M., Hussain, N.S., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Biological behaviour of Bonelike ® graft implanted in the tibia of humans (2005) Key Eng Mater, 17, pp. 1041-1044; Duarte, F., Santos, J.D., Afonso, A., Medical applications of Bonelike ® in maxillofacial surgery (2004) Adv Mater Forum, pp. 370-373; Lobato, J.V., Hussain, N.S., Botelho, C.M., Titanium dental implants coated with Bonelike ®: clinical case report (2006) Thin Solid Films, 515, p. 279; Coventry, M.B., Osteotomy of the upper portion of the tibia for degenerative arthritis of the knee: a preliminary report (1965) J Bone Joint Surg Am, 47, pp. 984-990; Coventry, M.B., Upper tibia osteotomy for gonarthrosis. The evolution of the operation in the last 18 years and long term results (1979) Orthop Clin North Am, 10, pp. 191-210; Coventry, M.B., Current concepts review. Upper tibia osteotomy for osteoarthritis (1985) J Bone Joint Surg Am, 67 A, pp. 1136-1140
Keywords: adult; aged; article; biomaterial; bone defect; Bone graft; bone growth; Bone Regeneration; Bone Substitutes; bone tissue; Bonelike; clinical article; controlled study; Female; histology; human; human tissue; Humans; implant; knee osteoarthritis; male; materials testing; Microscopy, Electron, Scanning; Middle Aged; molecular scaffold; Orthopaedic; orthopedics; Osseointegration; Osteoarthritis; osteotomy; porosity; Porous materials; priority journal; Prostheses and Implants; Scanning electron microscopy; tibia; Time Factors; Tissue engineering; tissue section; vascularization; ®

Cell-induced response by tetracyclines on human bone marrow colonized hydroxyapatite and Bonelike ® - Gomes, P.S.; Santos, J.D.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2008)
Semi-synthetic tetracyclines are commonly used antibiotics that also seem to play an important role in the modulation of the immuno-inflammatory imbalance, verified in several bone diseases. The association of a therapeutic agent (that prevents bacterial infection and induces tissue formation) to a biomaterial aiming to repair/regenerate bone defects could contribute to a more predictable clinical outcome. The present study intends to evaluate the proliferation and functional activity of osteoblast-induced human bone marrow cells, cultured on the surface of hydroxyapatite (HA) and Bonelike ®, in the presence of therapeutic concentrations of doxycycline and minocycline. First passage bone marrow cells were cultured for 35 days on the surface of HA and Bonelike ® discs, in the absence or presence of 1 μg ml
Cited By (since 1996): 9Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2007.12.006PubMed ID: 18291737Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Laboratório de Farmacologia e Biocompatibilidade Celular, Faculdade de Medicina Dentária, Universidade do Porto (FMDUP), Rua Dr. Manuel Pereira da Silva, s/n, 4200-392 Porto, Portugal; email: mhrf@portugalmail.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; doxycycline, 10592-13-9, 17086-28-1, 564-25-0; hydroxyapatite, 1306-06-5, 51198-94-8; minocycline, 10118-90-8, 11006-27-2, 13614-98-7; Alkaline Phosphatase, EC 3.1.3.1; Bone Substitutes; Calcium, 7440-70-2; Culture Media; Durapatite, 1306-06-5; Minerals; Tetracycline, 60-54-8Tradenames: BonelikeReferences: Chambers, H., Protein synthesis inhibitors and miscellaneous antibacterial agents (2006) Goodman and Gilman's - The Pharmacological Basis of Therapeutics, pp. 1173-1202. , Brunton L. (Ed), McGraw-Hill, Germany;Alkan, A., Erdem, E., Gunhan, O., Karasu, C., Histomorphometric evaluation of the effect of doxycycline on the healing of bone defects in experimental diabetes mellitus: a pilot study (2002) J Oral Maxillofac Surg, 60, p. 898; Buchter, A., Kleinheinz, J., Meyer, U., Joos, U., Treatment of severe peri-implant bone loss using autogenous bone and a bioabsorbable polymer that delivered doxycycline (Atridox TM) (2004) Brit J Oral Maxillofacial Surg, 42, pp. 452-456; Ramamurthy, N., Rifkin, B., Greenwald, R., Xu, J.-W., Liu, Y., Turner, G., Inhibition of matrix metalloproteinase-mediated periodontal bone loss in rats: a comparison of 6 chemically modified tetracyclines (2005) J Periodontol, 73, pp. 726-734; Golub, L., Ramamurthy, N., Kaneko, H., Sasaki, T., Rifkin, B., McNamara, T., Tetracycline administration prevents diabetes-induced osteopenia in the rat: initial observations (1990) Res Commun Chem Pathol Pharmacol, 68, p. 27; Williams, S., Wakisaka, A., Zeng, Q., Barnes, J., Martin, G., Wechter, W., Minocycline prevents the decrease in bone mineral density and trabecular bone in ovariectomized aged rats (1996) Bone, 19, pp. 637-644; Williams, S., Wakisaka, A., Zeng, Q., Barnes, J., Seyedin, S., Martin, G., Effect of minocycline on osteoporosis (1998) Adv Dental Res, 12, pp. 71-75; Pytlik, M., Folwarczna, J., Janiec, W., Effects of doxycycline on mechanical properties of bones in rats with ovariectomy-induced osteopenia (2004) Calcified Tissue Int, 75, pp. 225-230; Holmes, S., Still, K., Buttle, D., Bishop, N., Grabowski, P., Chemically modified tetracyclines act through multiple mechanisms directly on osteoclast precursors (2004) Bone, 35, pp. 471-478; Polson, A., Bouwsma, O., McNamara, T., Golub, L., Enhancement of alveolar bone formation after tetracycline administration in squirrel monkeys (2005) J Appl Res Clin Dent, pp. 32-42; Yamaguchi, A., Udagawa, T., Sawai, T., Transport of divalent cations with tetracycline as mediated by the transposon Tn10-encoded tetracycline resistance protein (1990) J Biol Chem, 265, pp. 4809-4813; Li, S., de Wijn, J., Layrolle, P., de Groot, K., Synthesis of macroporous hydroxyapatite scaffolds for bone tissue engineering (2002) J Biomed Mater Res, 61, pp. 109-120; Giannoudis, P., Dinopoulos, H., Tsiridis, E., Bone substitutes: an update (2005) Int J Care Injured, 365, p. 220; LeGeros, R., Properties of osteoconductive biomaterials: calcium phosphates (2002) Clin Orthop, 395, pp. 81-98; Suchanek, W., Yoshimura, M., Processing and properties of hydroxyapatite-based biomaterials for use as hard tissue replacement implants (1998) J Mater Res, 13, pp. 94-117; Lopes, M., Santos, J., Monteiro, F., Knowles, J., Glass reinforced hydroxyapatite: a comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-250; Hench, L., Bioactive materials: the potential for tissue regeneration (1998) J Biomed Mater Res, 41, pp. 511-518; Kellomaki, M., Niiranen, H., Puumanen, K.A.N., Waris, T., Tormala, P., Bioabsorbable scaffolds for guided bone, regeneration, and generation (2000) Biomaterials, 21, pp. 2495-2505; Santos, J., Reis, R., Monteiro, F., Knowles, J., Hastings, G., Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions structure and properties of the composites (1995) J Mater Sci Mat Med, 6, p. 348; Santos, J., Silva, P., Knowles, J., Talal, S., Monteiro, F., Reinforcement of hydroxyapatite by adding P 2O 5-CaO glasses with Na 2O, K 2O and MgO (1996) J Mater Sci Mat Med., 7, p. 187; Duarte, F., Santos, J., Afonso, A., Medical applications of Bonelike in maxillofacial surgery (2004) Mater Sci Forum, 370, pp. 455-456; Gutierres, M., Hussain, N., Afonso, A., Almeida, L., Cabral, A., Lopes, M., Biological behaviour of bonelike ® graft implanted in the tibia of humans (2005) Key Eng Mater, 1041, pp. 284-286; Brause, B., Infections with prostheses in bones and joints (2000) Mandell, Douglas and Bennett's Principles and Practice of Infectious Diseases. 5th ed., pp. 1196-1200. , Mandell G., Bennet J., and Dolin R. (Eds), Churchill Livingstone, Philadelphia; Darley, E., MacGowan, A., Antibiotic treatment of Gram-positive bone and joint infections (2004) J Antimicrobial Chemotherapy, 53, pp. 928-935; Zucchelli, G., Sforza, N., Clauser, C., Cesari, C., De Sanctis, M., Topical and systemic antimicrobial therapy in guided tissue regeneration (1999) J Periodontol, 70, pp. 239-247; Yukna, R., Sepe, W., Clinical evaluation of localized periodontosis defects treated with freeze-dried bone allografts combined with local and systemic tetracyclines (1982) Int J Periodontics Restorative Dent, 2, pp. 8-21; Shirtliff, M., Mader, J., Acute septic arthritis (2002) Clin Microbiol Rev, 15, pp. 527-544; Sunder, M., Babu, N., Victor, S., Kumar, K., Kumar, T., Biphasic calcium phosphates for antibiotic release (2005) Trends Biomater Artif Organs, 18, pp. 213-218; Lieberman, J., Daluiski, A., Einhorn, T., The role of growth factors in the repair of bone: biology and clinical applications (2002) J Bone Joint Surg, 84, pp. 1032-1044; Carson, J., Bostrom, M., Synthetic bone scaffolds and fracture repair (2007) Injury, 38, pp. S33-S70; Regí-Vallet, M., Balas, F., Colilla, M., Manzano, M., Drug confinement and delivery in ceramic implants (2007) Drug Metabol Lett, 1, pp. 37-40; Lin, T.-L., Lu, F.-M., Conroy, S., Sheu, M.-S., Su, S.-H., Tang, L., Antimicrobial coatings: a remedy for medical device-related infections (2001) Med Device Technol., 12, pp. 26-30; Beardmore, A., Brooks, D., Wenke, J., Thomas, D., Effectiveness of local antibiotic delivery with an osteoinductive and osteoconductive bone-graft substitute (2005) J Bone Joint Surg, 87, pp. 107-112; Gomes, P., Fernandes, M., Effect of therapeutic levels of doxycycline and minocycline in the proliferation and differentiation of human bone marrow osteoblastic cells (2007) Arch Oral Biol, 52, pp. 251-259; Coelho, M., Fernandes, M., Human bone cell cultures in biocompatibility testing Part II. Effect of ascorbic acid, β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Jørgensen, N., Henriksena, Z., Sørensena, O., Civitelli, R., Dexamethasone, BMP-2, and 1,25-dihydroxyvitamin D enhance a more differentiated osteoblast phenotype: validation of an in vitro model for human bone marrow-derived primary osteoblasts (2004) Steroids, 69, pp. 219-226; Sakellari, D., Goodson, J., Socransky, S., Kolokotronis, A., Konstantinidis, A., Concentration of 3 tetracyclines in plasma, gingival crevice fluid and saliva (2000) J Clin Periodontol, 27, pp. 53-60; Stein, G., Lian, J., Molecular mechanisms mediating proliferation/differentiation interrelationships during progressive development of the osteoblast phenotype (1993) Endocr Rev, 14, pp. 424-442; Zhang, Y., Lopes, M., Santos, J., CaO-P 2O 5 Glass ceramics containing bioactive phases: crystallization and in vitro bioactivity studies (2001) Key Eng Mater, 192, pp. 643-646; Lopes, M., Knowles, J., Santos, J., Monteiro, F., Olsen, I., Direct and indirect effects of P 2O 5-glass reinforced hydroxyapatite on the growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Costa, M., Gutierres, M., Almeida, L., Lopes, M., Santos, J., Fernandes, M., In vitro mineralisation of human bone marrow cells cultured on Bonelike (2004) Key Eng Mater, pp. 254-256. , (821-4); Lopes, M., Santos, J., Monteiro, F., Ohtsuki, C., Osaka, A., Kaneko, S., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Gutierres, M., Hussain, N., Lopes, M., Afonso, A., Cabral, A., Almeida, L., Histological and scanning electron microscopy analyses of bone/implant interface using the novel Bonelike ® synthetic bone graft (2006) J Ortho Res, 24, p. 953; Kima, H.-W., Leea, E.-J., Kima, H.-E., Salihb, V., Knowles, J., Effect of fluoridation of hydroxyapatite in hydroxyapatite-polycaprolactone composites on osteoblast activity (2005) Biomaterials, 26, pp. 4395-4404; Williams, S., Barnes, J., Wakisaka, A., Ogasa, H., Liang, C., Treatment of osteoporosis with MMP inhibitors (1999) Ann NY Acad Sci, 878, pp. 191-200; Schwartz, Z., Lohmann, C., Wieland, M., Cochran, D., Dean, D., Textor, M., Osteoblast proliferation and differentiation on dentin slices are modulated by pretreatment of the surface with tetracycline or osteoclasts (2000) J Periodontol, 71, pp. 586-597; Bettany, J., Wolowacz, R., Tetracycline derivatives induce apoptosis selectively in cultured monocytes and macrophages but not in mesenchymal cells (1998) Adv Dent Res, 12, pp. 136-143; Duewelhenke, N., Krut, O., Eysel, P., Influence on mythochondria and cytotoxicity of different antibiotics administered in high concentrations on primary human osteoblasts and cell lines (2007) Antimicrobial Agents and Chemotherapy, 51, pp. 54-63; Golub, L., Wolff, M., Roberts, S., Lee, H.-M., Leung, M., Payonk, G., Treating periodontal diseases by blocking tissue-destructive enzymes (1994) JADA, 125, pp. 163-169; Woessner, J., Nagase, H., Inhibition of MMPs (2000) MMPs and Timps, pp. 109-125. , Woessner J., and Nagase H. (Eds), Oxford University Press, Oxford; Golub, L., Ramamurthy, N., McNamara, T., Gomes, B., Wolff, M., Casino, A., Tetracyclines inhibit tissue collagenase activity. A new mechanism in the treatment of periodontal disease (1984) J Periodontal Res, 19, pp. 651-655; Yu, Z., Ramamurthy, N., Leung, M., Chang, K., McNamara, T., Golub, L., Chemically-modified tetracycline normalizes collagen metabolism in diabetic rats: a dose-response study (1993) J Periodontal Res, 28, pp. 420-428; Karimbux, N., Ramamurthy, N., Golub, L., Nishimura, I., The expression of collagen I and XII on RNAs in porphyromonas gingivalis-induced periodontitis in rats: The effect of doxycycline and chemically-modified tetracycline (CMT-1) (1998) J Periodontol, 69, pp. 39-40; Ramamurthy, N., Pirila, E., Lee, H.-M., Delayed wound healing, altered collagen level and keratinocyte growth factor expression in skin of ovariectomized rat is normalized by estrogen or chemically modified doxycycline (2003) Menopause - The State of the Art in Research and Management. The Proceedings of the Tenth World Congress, pp. 236-243. , Schneider H. (Ed), Parthenon Publishing Group, New York; Gurkan, A., Çunarcuk, S., Huseyinov, A., Adjunctive subantimicrobial dose doxycycline: effect on clinical parameters and gingival crevicular fluid transforming growth factor-b 1 levels in severe, generalized chronic periodontitis (2005) J Clin Periodontol, 32, pp. 244-253; Caton, J., Evaluation of Periostat for patient management (1999) Compend Contin Edu Dent, 20, pp. 451-456; Salasznyk, R., Williams, W., Boskey, A., Batorsky, A., Plopper, G., Adhesion to vitronectin and collagen I promotes osteogenic differentiation of human mesenchymal stem cells (2004) J Biomed Biotechnol, 1, pp. 24-34; Gerstenfeld, L., Chipman, S., Kelly, C., Hodgens, K., Lee, D., Landis, W., Collagen expression, ultrastructural assembly, and mineralization in cultures of chicken embryo osteoblasts (1988) J Cell Biol, 106, pp. 979-989
Keywords: adult; alkaline phosphatase; alkaline phosphatase bone isoenzyme; antimicrobial activity; article; Bacteria (microorganisms); bone infection; bone marrow cell; Bone Marrow Cells; Bone Substitutes; Bonelike; Calcium; calcium phosphate; Cell culture; cell function; cell proliferation; cell survival; cell viability; Cells, Cultured; concentration response; controlled study; Culture Media; culture medium; doxycycline; Durapatite; enzyme activity; extracellular matrix; glass; human; human cell; Humans; hydroxyapatite; implant; Microscopy, Electron, Scanning; Middle Aged; Minerals; minocycline; osteoblast; Osteoblasts; priority journal; Scanning electron microscopy; stroma cell; Tetracycline; tetracycline derivative; Tetracyclines; X-Ray Diffraction

Chromatographic pattern classification - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (IEEE Transactions on Biomedical EngineeringIEEE Trans. Biomed. Eng., 2008)
In this paper, we propose and evaluate methodologies for the classification of images from thin-layer chromatography. Each individual sample is characterized by an intensity profile that is further represented into a feature space. The first steps of this process aim at obtaining a robust estimate of the intensity profile by filtering noise, reducing the influence of background changes, and by fitting a mixture of Gaussians. The resulting profiles are represented by a set of appropriate features trying to characterize the state of nature, here spread out over four classes, one for normal subjects and the other three corresponding to lysosomal diseases, which are disorders responsible for severe nerve degeneration. For classification purposes, a novel solution based on a hierarchical structure is proposed. The main conclusion of this paper is that an automatically generated decision tree presents better results than more conventional solutions, being able to deal with the natural imbalance of the data that, as consequence of the rarity of lysosomal disorders, has very few representative cases in the disease classes when compared with the normal population. © 2008 IEEE.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusArt. No.: 8CODEN: IEBEAdoi: 10.1109/TBME.2008.919852PubMed ID: 18714832Language of Original Document: EnglishCorrespondence Address: Sousa, A. V.; Instituto de Engenharia Biomédica (INEB), Instituto Superior de Engenharia Do Porto, 4200-465 Porto, Portugal; email: ats@isep.ipp.ptChemicals/CAS: Hydrolases, EC 3.-References: Keir, G., Winchester, B., Clayton, P., Carbohydrate-deficient glycoprotein syndromes: Inborn errors of protein glycosylation (1999) Ann. Clin. Biochem, 36 (1), pp. 20-36;Durand, G., Seta, N., Protein glycosylation and diseases: Blood and urinary oligosaccharides as markers for diagnosis and therapeutic monitoring (2000) Clin. Chem, 46, pp. 795-805; Scriver, S., Beaudet, A., Sly, W., Valle, D., (2001) The Metabolic Bases of Inherited Disease, 3. , New-York: McGraw-Hill; Pinto, R., Caseiro, C., Lemos, M., Lopes, L., Fontes, A., Miranda, M., Prevalence of lysosomal storage diseases in Portugal (2004) Eur. J. Hum. Genet, 12, pp. 87-92; Friedman, R., Williams, M., Moser, H., Kolodny, E., Improved thin-layer chromatographic method in the diagnosis of mannosidosis (1978) Clin. Chem, 24, pp. 1576-1577; Kurczynski, T., Kendzierski, K., Sewell, A., Kuczynski, T., Urinary oligosaccharides in pregnant or lactating women: Pitfall in screening (1993) Clin. Chem, 39, pp. 2346-2347; Sewell, A., Urinary oligosaccharides (1991) Techniques Diagnostic Human Biochemical Genetics, pp. 219-231. , New York: Wiley; Reich, E., Blatter, A., Modern TLC: A key technique for identification and quality control of botanicals and dietary supplements (2005) J. Planar Chromatogr. - Modern TLC, 18, pp. 34-37. , Jan./Feb; Duvdevani-Bar, S., Edelman, S., Visual recognition and categorization on the basis of similarities to multiple class prototypes (1999) Int. J. Comput. Vis, 33, pp. 201-228; Pekalska, E., Duin, R., Dissimilarity representations allow for building good classifiers (2002) Pattern Recognit. Lett, 23, pp. 943-956; Goldstone, R., Son, J., Similarity (2005) Cambridge Handbook of Thinking and Reasoning, pp. 13-36. , K. Holyoak and R. Morrison, Eds. Cambridge, MA: Cambridge Univ. Press; Lavine, B., Clustering and classification of analytical data (2000) Encyclopedia of Analytical Chemistry: Instrumentation and Applications, pp. 9689-9710. , R. Meyers, Ed. Chichester, U.K, Wiley; Japkowicz, N., Learning from imbalanced data sets: A comparison of various strategies (2000) Proc. Learn. Imbalanced Data, pp. 10-15; Weiss, G., Mining with rarity: A unifying framework (2004) Sigkdd Explor, 6, pp. 7-19; Kubat, M., Holte, R., Matwin, S., Machine learning for the detection of oil spills in satellite radar images (1998) Mach. Learn, 30, pp. 195-215; Tax, D., One-class classification; concept-learning in the absence of counter-examples, (2001), ASCI, pp. 1-190. , Ph.D. dissertation, Delft Univ. Technol, Dissertation Ser, ppSousa, A., Aguiar, R., Mendonça, A., Campilho, A., Automatic lane and band detection in images of thin layer chromatography (2004) Lecture Notes in Computer Science, 3212, pp. 158-165. , Image Analysis and Recognition, New York: Springer-Verlag; Schwedt, G., (1997) The Essential Guide to Analytical Chemistry, , New York: Wiley; Bajla, I., Hollander, I., Fluch, S., Burg, K., Kollar, M., An alternative method for electrophoretic gel image analysis in the GelMaster software (2005) Comput. Methods Programs Biomed, 77, pp. 209-231; Eibrand, R., Kennedy, P., Cotter, D., MacEvilly, U., Wu, B., Analysis of Atlantic salmon skin mucus: COPS - A computer-based system for protein pattern analysis of 1D SDS-PAGE gels (2003) Proc. IEEE Symp. Bioinf. BioEng, pp. 45-52; Gerasimov, A., Use of the software processing of scanned chromatogram images in quantitative planar chromatography (2004) J. Anal. Chem, 59, pp. 348-353; Goulding, P., (2000) Electrophoresis Gel Analysis Software: Important Aspects, p. 14. , Cambridge, U.K, UVItec Ltd; Jedra, M., El Khattabi, N., Limouri, M., Essaid, A., Recognition of seed varieties using a time-delay neural network: Analysis of electrophoretic images (1999) Comput. Electron. Agric, 22, pp. 1-10; Machado, A., Campos, M., Siqueira, A., Carvalho, O., An iterative algorithm for segmenting lanes in gel electrophoresis images (1997) Proc. Comput. Graph. Image Process. X Braz. Symp, pp. 140-146. , Campos do Jordao, Brazil, Oct; Ye, X., Suen, C., Cheriet, M., Wang, E., A recent development in image analysis of electrophoresis gels (1999) Proc. Vis. Interface, pp. 432-438; Shadle, S., Allen, D., Guo, H., Pogozelski, W., Bashkin, J., Tullius, T., Quantitative analysis of electrophoresis data: Novel curve fitting methodology and its application to the determination of a protein-DNA binding constant (1997) Nucleic Acids Res, 25, pp. 850-860; Bajla, I., Hollander, I., Burg, K., Improvement of electrophoretic gel image analysis (2001) Meas. Sci. Rev, 1, pp. 5-10; Bajla, I., Hollander, I., Burg, K., Fluch, S., A novel approach to quantitative analysis of electrophoretic gel images of DNA fragments (2002) Proc. IEEE Int. Symp. Biomed. Imag, pp. 899-902; Lonni, A., Scarminio, I., Silva, L., Ferreira, D., Differentiation of species of Baccharis Genus by HPLC and chemometrics methods (2003) Anal. Sci, 19, pp. 1013-1017; Beltrán, N., Duarte-Mermoud, M., Salah, S., Bustos, M., Feature selection algorithms using Chilean wine chromatograms as examples (2005) J. Food Eng, 67, pp. 483-490; Landgrebe, D., Information extraction principles and methods for multispectral and hyperspectral image data (2000) Information Processing for Remote Sensing, , Hackensack, NJ: World Scientific, ch. 1; Landgrebe, D., Hyperspectral image data analysis as a high dimensional signal processing problem (2002) IEEE Signal Process. Mag, 19 (1), pp. 17-28. , Jan; Jimenez, L., Landgrebe, D., Hyperspectral data analysis and feature reduction via projection pursuit (1999) IEEE Trans. Geosci. Remote Sens, 37 (6), pp. 2653-2667. , Nov; Jimenez, L., Landgrebe, D., Supervised classification in high- dimensional space: Geometrical, statistical, and asymptotical properties of multivariate data (1998) IEEE Trans. Syst., Man, Cybern, 28 (1), pp. 39-54. , Pt. C, Feb; Marques deSá, J., (2001) Pattern Recognition - Concepts, Methods and Applications, , Berlin, Germany: Springer-Verlag; Heijden, F., Duin, R., Ridder, D., Tax, D., (2004) Classification, Parameter Estimation and State Estimation, , New York: Wiley; Dudoit, S., Fridlyand, J., Speed, T., Comparison of discrimination methods for the classification of tumors using gene expression data (2002) J. Amer. Stat. Assoc, 97, pp. 77-87; Zomer, S., Brereton, R., Carter, J., Eckers, C., Support vector machines for the discrimination of analytical chemical data: Application to the determination of tablet production by pyrolysis-gas chromatography-mass spectrometry (2004) Analyst, 129, pp. 175-181; Zomer, S., Guillo, C., Brereton, R., Hanna-Brown, M., Toxicological classification of urine samples using pattern recognition techniques and capilarity electrophoresis (2003) Anal. Bioanal. Chem, 378, pp. 2008-2020; Fan, X., Bai, J., Shen, P., Diagnosis of breast cancer using HPLC metabonomics fingerprints coupled with computational methods (2005) 27th Annu. Conf. Eng. Med. Biol, pp. 6081-6084. , Shanghai, China; Skurichina, M., Raudys, S., Duin, R., K-nearest neighbors directed noise injection in multilayer perceptron training (2000) IEEE Trans. Neural Netw, 11 (2), pp. 504-511. , Mar; Ha, T., Bunke, H., Off-line, handwritten numeral recognition by perturbation method (1997) IEEE Trans. Pattern Anal. Mach. Intell, 19, pp. 535-539; Lee, S., Noisy replication in skewed binary classification (2000) Comput. Stat. Data Anal, 34, pp. 165-191; Demant, C., Streicher-Abel, B., Waszkewitz, P., (1999) Industrial Image Processing, , New York: Springer-Verlag; Dempster, A., Laird, N., Rubin, D., Maximum likelihood from incomplete data via the EM algorithm (1977) J. Roy. Stat. Soc. B, 39 (1), pp. 1-38; Moré, J., Sorensen, D., Computing a trust region step (1983) SIAM J. Sci. Stat. Comput, 4, pp. 553-572; Byrd, R., Schnabel, R., Shultz, G., Approximate solution of the trust region problem by minimization over two-dimensional subspaces (1988) Math. Program, 40, pp. 247-263; Sousa, A., Mendonça, A., Campilho, A., Aguiar, R., Miranda, C., Feature extraction for classification of thin-layer chromatography images (2005) Lecture Notes in Computer Science, 3656, pp. 974-981. , Image Analysis and Recognition, New York: Springer-Verlag; Ripley, B., (2004) Pattern Recognition and Neural Networks, , New York: Cambridge Univ. Press; Visa, S., Ralescu, A., Learning imbalanced and overlapping classes using fuzzy sets (2003) ICML 2003, Workshop Learn. Imbalanced Datasets, 2. , presented at the, Washington, DC
Keywords: Acoustic variables control; Algorithms; article; Chromatographic analysis; Chromatographic pattern features; Chromatographic profiles; Chromatography; Chromatography, Thin Layer; Classification; Diagnosis, Computer-Assisted; Gaussian noise (electronic); Hierarchical classifier; Humans; Hydrolases; imaging; Lysosomal Storage Diseases; lysosome storage disease; mathematical analysis; nerve degeneration; noise; normal distribution; Pattern recognition; Pattern Recognition, Automated; Reproducibility of Results; sensitivity and specificity; Urinalysis

A clinical report of bone regeneration in maxillofacial surgery using bonelike® synthetic bone graft - Sousa, R.C.; Lobato, J.V.; Maurício, A.C.; Hussain, N.S.; Botelho, C.M.; Lopes, M.A.; Santos, J.D. (Journal of Biomaterials ApplicationsJ. Biomater. Appl., 2008)
The objective of this study is to evaluate the osteoconductivity and bioactivity of the Bonelike® graft in repairing surgical cystic bone defects. Bonelike® is implanted in 11 patients, aged between 24 and 53 years with a mean age of 36 years, consisting of 5 men and 6 women. According to the standard follow up protocols, radiological examinations are performed and Bonelike® /bone retrieved samples have been analyzed histologically using non-decalcified sections obtained perpendicular to bone length axis. Radiographic examination and histological results clearly demonstrate an extensive new bone formation apposed on Bonelike® granules with a significant degree of maturation. These clinical applications in maxillary bone defects indicate perfect bone bonding between new bone formed and Bonelike® granules, along with partial surface biodegradation. This quick and effective osteoconductive response from Bonelike® may reduce the time needed to reconstruct the bone defected area of patients. © 2008 Sage Publications.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JBAPEdoi: 10.1177/0885328207078260Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua Campo Alegre 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Bone SubstitutesReferences: Mohamed, A., Sudha, K., Kim, F., Karl, K., Scott, P.B., Bone Graft Substitutes (2003) Cell Based Approaches for Bone Graft Substitutes, p. 127. , In: Laurencin, C.T. (ed.), Chapter 7 ASTM - International, USA;Mellonig, J.T., Prewett, A.B., Moyer, M.P., HIV Inactivation in a Bone Allograft (1992) J. Periodontol., 63, p. 979; Buck, B.E., Malinin, T.I., Brown, M.D., Bone Transplantation and Human Immunodeficiency Virus. An Estimate of Risk of Acquired Immunodeficiency Syndrome (AIDS) (1989) Clin. Orthop., 240, p. 129; Mary, E.A.R., Raymond, A.Y., Bone Replacement Grafts - The Bone Substitutes (1998) Dent. Clin. North Am., 42 (3), p. 491; Doron, I.I., Amy, L.L., Bone Graft Substitutes (2002) Oper. Tech. Plast. Reconsr. Surg., 9 (4), p. 151; Wright, S., Commentary The Bone-Graft Market in Europe, in Emerging Technologies in Orthopedics I: Bone Graft Substitutes (1999) Bone Growth Stimulators and Bone Growth Factors By Datamonitor Plc, p. 591; Knaack, D., Goad, M.E.P., Aiolova, M., Christian, R., Ali, T., Promod, C., Duke Lee, D., Resorbable Calcium Phosphate Bone Substitute (1998) J. Biomed. Mater. Res., 43, p. 399; Frayssinet, P., Trouillet, J.L., Rouquet, N., Azimus, E., Autefage, A., Osseointegration Macroporous Calcium Phosphate Ceramics Having a Different Chemical Composition (1993) Biomaterials, 14, p. 423; Klein, C.P.A.T., Driessen, A.A., Groot de, K., van den Hooff, A., Biodegradation Behavior of Various Calcium Phosphate Materials in Bone Tissue (1983) J. Biomed. Mater. Res., 17, p. 769; Daculsi, G., Biphasic Calcium Phosphate Concept Applied to Artificial Bone, Implant Coating and Injectable Bone Substitute (1998) Biomaterials, 19, p. 1473; Santos, J.D., Hastings, G.W., Knowles, J.C., Sintered Hydroxyapatite Compositions and Method for the Preparation Thereof (1999) Worldwide Applications, , (PCT), Patent No. 1 189 851; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass Reinforced Hydroxyapatite: A Comprehensive Study of the Effect of Glass Composition on the Crystallography of the Composite (1998) J. Biomed. Mater. Res., 39, p. 244; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced Hydroxyapatite Composites: Fracture Toughness and Hardness Dependence on Microstructural Characteristics (1999) Biomaterials, 20, p. 2085; Lopes, M.A., Silva, R.F., Monteiro, F.J., Santos, J.D., Microstructural Dependence of Young's and Shear Moduli of P 2 O 2 Glass Reinforced Hydroxyapatite for Biomedical Applications (2000) Biomaterials, 21, p. 749; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., Push-out Testing and Histological Evaluation of Glass Reinforced Hydroxyapatite Composites Implanted in the Tibia of Rabbits (2001) J. Biomed. Mater. Res., 54, p. 463; Lobato, J.V., Hussain, N.S., Botelho, C.M., Rodrigues, J.M., Luís, A.L., Maurício, A.C., Lopes, M.A., Santos, J.D., Assessment of the Potential of Bonelike® Graft for Bone Regeneration by using an Animal Model (2005) Key. Eng. Mater., 877, pp. 284-286; Lobato, J.V., Hussain, N.S., Botelho, C.M., Mauricio, A.C., Afonso, A., Ali, N., Santos, J.D., Assessment of Bonelike® Graft with a Resorbable Matrix using an Animal Model (2006) Thin Solid Films, 515, p. 362; Duarte, F., Santos, J.D., Afonso, A., Medical Applications of Bonelike® in Maxillofacial Surgery (2004) Mater. Sci. Forum, 370, pp. 455-456; Gutierres, M., Hussain, N.S., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Santos, J.D., Biological Behaviour of Bonelike® Graft Implanted in Tibia of Humans (2005) Key Eng. Mater., 1041, pp. 284-286; LeGeros, R.Z., Properties of Osteoconductive Biomaterials: Calcium Phosphates (2002) Clin. Orthop., 395, p. 81; Robert, D.A.G., Hanneke, G.T., Ronald, J.H., Buma, P., Mechanism of Bone Incorporation of β-TCP Bone Substitute in Open Wedge Tibial Osteotomy in Patients (2005) Biomaterials, 26, p. 6713; Hirotsugu, H., Norio, A., Kimimitsu, O., Noritaka, F., Ohnishi, H., Okada, A., Nomura, S., Maeda, T., A Histological Evaluation on Self setting α-tricalcium Phosphate Applied in the Rat Bone Cavity (2004) Biomaterials, 25, p. 431; Meinel, L., Betz, O., Fajardo, R., Hofmann, S., Nazarian, A., Cory, E., Hilbe, M., Kirker-Head, C., Silk Based Biomaterials to Heal Critical Sized Femur Defects (2006) Bone, 39, p. 922; Lim, S.C., Lee, M.J., Yeo, H.H., Effects of Various Implant Materials on Regeneration of Calvarial Defects in Rats (2000) Pathol. Int., 50, p. 594; Carano, R.A.D., Filvaroff, E.H., Angiogenesis and Bone Repair (2003) Drug Discov. Today, 21, p. 980; Gutierres, M., Hussain, N.S., Lopes, M.A., Afonso, A., Cabral, A.T., Almeida, L., Santos, J.D., Histomorphometric Measurements Histological and SEM Analyses of bone/ implant Interface: Clinical Trials using Bonelike® Granules (2006) J. Orthop. Res., 24, p. 953
Keywords: adult; article; Bioactivity; Bone; bone prosthesis; Bone Regeneration; Bone Substitutes; bone transplantation; Bonelike®; clinical trial; facial bone; Facial Bones; Female; Histological studies; histology; human; Humans; Implants (surgical); instrumentation; male; Maxillofacial surgery; methodology; Middle Aged; oral surgery; Pathology; Radiography; Radiology; Regeneration; Surgery; Surgery, Oral; Synthetic bone graft; treatment outcome

Data classification with multilayer perceptrons using a generalized error function - Silva, L.M.; Marques de Sá, J.; Alexandre, L.A. (Neural NetworksNeural Netw., 2008)
The learning process of a multilayer perceptron requires the optimization of an error function E (y, t) comparing the predicted output, y, and the observed target, t. We review some usual error functions, analyze their mathematical properties for data classification purposes, and introduce a new one, E Exp, inspired by the Z-EDM algorithm that we have recently proposed. An important property of E Exp is its ability to emulate the behavior of other error functions by the sole adjustment of a real-valued parameter. In other words, E Exp is a sort of generalized error function embodying complementary features of other functions. The experimental results show that the flexibility of the new, generalized, error function allows one to obtain the best results achievable with the other functions with a performance improvement in some cases. © 2008 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: NNETEdoi: 10.1016/j.neunet.2008.04.004PubMed ID: 18572384Language of Original Document: EnglishCorrespondence Address: Silva, L.M.; INEB-Instituto de Engenharia Biomédica, Porto, Portugal; email: lmsilva@fe.up.ptReferences: Baum, E.B., Wilczek, F., Supervised learning of probability distributions by neural networks (1987) NIPS, pp. 52-61. , Anderson D.Z. (Ed), American Institute of Physics;Bishop, C., (1995) Neural networks for pattern recognition, , Oxford University Press; Blake, C., & Merz, C. (1998). UCI repository of machine learning databases. University of California, Irvine, Dept. of Information and Computer SciencesForina, M., Armanino, C., Eigenvector projection and simplified non-linear mapping of fatty acid content of italian olive oils (1981) Annali di Chimica (Rome), 50, pp. 127-155; Gish, H. (1990). A probabilistic approach to the understanding and training of neural network classifiers. In Proceedings of the 1990 IEEE international conference on acoustics, speech, and signal processingHampshire, J., Waibel, A., A novel objective function for improved phoneme recognition using time-delay neural networks (1990) IEEE Transactions on Neural Networks, 1 (2), pp. 216-228; Hinton, G.E., Connectionist learning procedures (1989) Artificial Intelligence, 40 (1-3), pp. 185-234; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, 3, pp. 79-87; Møller, M. (1993). Efficient training of feed-forward neural networks. Ph.D. thesis. Computer Science Department - Aarhus UniversityMarques de Sá, J., (2001) Pattern recognition: Concepts, methods and applications, , Springer Verlag; Matsuoka, K., & Yi, J. (1991). Backpropagation based on the logarithmic error function and elimination of local minima. In Proceedings of the 1990 IEEE international joint conference on neural networksRichard, M., Lippmann, R., Neural network classifiers estimate bayesian a posteriori probabilities (1991) Neural Computation, 3, pp. 461-483; Santos, J., Alexandre, L., & Marques de Sá, J. (2004). The error entropy minimization algorithm for neural network classification. In int. conf. on recent advances in soft computingSilva, L., Alexandre, L., Marques de Sá, J., Neural network classification: Maximizing zero-error density (2005) LNCS, 3686, pp. 127-135. , ICAPR 2005; Silva, L., Alexandre, L.A., & Marques de Sá, J. (2006). New developments of the Z-EDM algorithm. In Proceedings of the sixth international conference intelligent systems design and applications: Vol. 1 (pp. 1067-1072)Silva, L., Marques de Sá, J., & Alexandre, L. (2005). Neural network classification using Shannon's entropy. In European symposium on artificial neural networksSilverman, B., (1986) Density estimation for statistics and data analysis, , Chapman & Hall; Solla, S.A., Levin, E., Fleisher, M., Accelerated learning in layered neural networks (1988) Complex Systems, 2 (6), pp. 625-639
Keywords: algorithm; Algorithms; analytical error; article; calculation; Classification; Complementary features; Cybernetics; data analysis; Data classification; Data classifications; Data Interpretation, Statistical; Electric loads; entropy; Error functions; learning; Learning processes; mathematical analysis; Mathematical properties; Models, Statistical; Multilayer neural networks; Multilayer perceptron; Multilayer perceptrons; Multilayers; Neural networks; Neural Networks (Computer); Pattern recognition systems; perceptron; Performance improvements; priority journal; Probability density function

Dissimilarity-based classification of chromatographic profiles - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Pattern Analysis and ApplicationsPattern Anal. Appl., 2008)
This paper proposes a non-parametric method for the classification of thin-layer chromatographic (TLC) images from patterns represented in a dissimilarity space. Each pattern corresponds to a mixture of Gaussian approximation of the intensity profile. The methodology comprises various phases, including image processing and analysis steps to extract the chromatographic profiles and a classification phase to discriminate among two groups, one corresponding to normal cases and the other to three pathological classes. We present an extensive study of several dissimilarity-based approaches analysing the influence of the dissimilarity measure and the prototype selection method on the classification performance. The main conclusions of this paper are that, Match and Profile-difference dissimilarity measures present better results, and a new prototype selection methodology achieves a performance similar or even better than conventional methods. Furthermore, we also concluded that simplest classifiers, such as k-NN and linear discriminant classifiers (LDCs), present good performance being the overall classification error less than 10% for the four-class problem. © 2008 Springer-Verlag London Limited.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1007/s10044-008-0113-2Language of Original Document: EnglishCorrespondence Address: Sousa, A. V.; Instituto Superior de Engenharia do Porto, Rua Dr. António Bernardino Almeida, 431, 4200-072 Porto, Portugal; email: ats@isep.ipp.ptReferences: Reich, E., Blatter, A., Modern TLC: A key technique for identification and quality control of botanicals and dietary supplements (2004) Inside Laboratory Management-AOC International;Sousa, A.V., Aguiar, R., Mendonça, A.M., Campilho, A., Automatic lane and band detection in images of thin layer chromatography (2004) LNCS, 3212, pp. 158-165. , Proceedings of image analysis and recognition: international conference, ICIAR 2004, Porto Springer, Heidelberg; Keir, G., Winchester, B.G., Clayton, P., Carbohydrate-deficient glycoprotein syndromes: Inborn errors of protein glycosylation (1999) Ann Clin Biochem, 36, pp. 20-36. , Pt 1; Durand, G., Seta, N., Protein glycosylation and diseases: Blood and urinary oligosaccharides as markers for diagnosis and therapeutic monitoring (2000) Clin Chem, 46, pp. 795-805; Schwedt, G., (1997) The Essential Guide to Analytical Chemistry, , Wiley New York; Bajla, I., Hollander, I., Fluch, S., Burg, K., Kollar, M., An alternative method for electrophoretic gel image analysis in the GelMaster software (2005) Comput Methods Programs Biomed, 77, pp. 209-231; Eibrand, R., Kennedy, P., Cotter, D., MacEvilly, U., Wu, B., Analysis of atlantic salmon skin mucus: COPS-a computer-based system for protein pattern analysis of 1D SDS-PAGE gels (2003) Proceedings of the Third IEEE Symposium on Bioinformatics and Bioengeneering; Gerasimov, A.V., Use of the software processing of scanned chromatogram images in quantitative planar chromatography (2004) J Anal Chem, 59, pp. 348-353; (2000) Gel Analysis Software: Important Aspects, , Goulding electrophoresis PN UVItec Ltd; Jedra, M., El Khattabi, N., Limouri, M., Essaid, A., Recognition of seed varieties using a time-delay neural network: Analysis of electrophoretic images (1999) Comput Electron Agric, 22, pp. 1-10; MacHado, A.M.C., Campos, M.F.M., Siqueira, A.M., De Carvalho, O.S.F., An iterative algorithm for segmenting lanes in gel electrophoresis images. Computer graphics and image processing (1997) Proceedings of X Brazilian Symposium, pp. 140-146; Ye, X., Suen, C.Y., Cheriet, M., Wang, E., A recent development in image analysis of electrophoresis gels (1999) Vision Iterface 99, , Trois-Rivieres, Canada; Wang, D., Keller, J.M., Carson, C.A., Pulsed-field gel electrophoresis pattern recognition of bacterial DNA: A systemic approach (2001) Pattern Anal Appl, 4, pp. 244-255; Shadle, S.E., Allen, D.F., Guo, H., Pogozelski, W.K., Bashkin, J.S., Tullius, T.D., Quantitative analysis of electrophoresis data: Novel curve fitting methodology and its application to the determination of a protein-NA binding constant (1997) Nucleic Acids Res, 25, pp. 850-860; Bajla, I., Hollander, I., Burg, K., Improvement of electrophoretic gel image analysis (2001) Measurement Science Review, 1; Bajla, I., Hollander, I., Burg, K., Fluch, S., (2002) A Novel Approach to Quantitative Analysis of Electrophoretic Gel Images of DNA Fragments, pp. 899-902. , IEEE international symposium on biomedical imaging Washington; Lavine, B.K., Meyers, R.A., Clustering and classification of analytical data (2000) Encyclopedia of Analytical Chemistry: Instrumentation and Applications, pp. 9689-9710. , Wiley Chichester; Lonni, A., Scarminio, I., Silva, L., Ferreira, D., Differentiation of species of bacharis genus by HPLC and chemometrics methods (2003) Analytical Sciences, 19; Beltrán, N.H., Duarte-Mermoud, M.A., Salah, S.A., Bustos, M.A., Feature selection algorithms using Chilean wine chromatograms as examples (2005) J Food Eng, 67, pp. 483-490; Landgrebe, D., Information extraction principles and methods for multispectral and hyperspectral image data (1999) Proceedings of Information Processing for Remote Sensing, , World Scientific, Singapore; Landgrebe, D., Hyperspectral image data analysis as a high dimensional signal processing problem (2002) IEEE Signal Process Mag, 19, pp. 17-28; Jimenez, L., Landgrebe, D., Hyperspectral data analysis and feature reduction via projection pursuit (1999) IEEE Trans Geosci Remote Sens, 37, pp. 2653-2667; Jimenez, L.O., Landgrebe, D.A., Supervised classification in high-dimensional space: Geometrical, statistical, and asymptotical properties of multivariate data (1998) IEEE Transaction on Systems Man, and Cybernetics-Part C: Applications and Reviews, 28; Paclik, P., Duin, R.P.W., Dissimilarity-based classification of spectra: Computational issues (2003) Real-Time Imaging, 9, pp. 237-244; Paclik, P., Duin, R.P.W., Classifying spectral data using relational representation (2003) Proceedings of Spectral Imaging Workshop, , Graz; Pekalska, E., Paclik, P., Duin, R.P.W., A generalized kernel approach to dissimilarity-based classification (2001) J Mach Learn Res, 2, pp. 175-211; Pekalska, E., Duin, R.P.W., Dissimilarity representations allow for building good classifiers (2002) Pattern Recogn Lett, 23, pp. 943-956; Pekalska, E., Duin, R.P.W., (2005) The Dissimilarity Representation for Pattern Recognition-foundations and Applications, 64. , World Scientific, Singapore; Pekalska, E., Duin, R.P.W., Paclik, P., Prototype selection for dissimilarity-based classifiers (2006) Pattern Recogn, 39, pp. 189-208; Harol, A., Lai, C., Pekalska, E., Duin, R.P.W., Pairwise feature evaluation for constructing reduced representations (2007) Pattern Anal Appl, 10, pp. 55-68; Dubuisson, M.-P., Jain, A.K., A modified Hausdorff distance for object matching (1994) Proceedings of International Conference on Pattern Recognition, pp. 566-568. , Jerusalem; Heijden, F., Robert, P.W.D., Ridder, D., Tax, D.M.J., (2004) Classification, Parameter Estimation and State Estimation, , Wiley, New York; Dasarathy, B.V., Sánchez, J.S., Townsend, S., Nearest neighbour editing and condensing tools-synergy exploitation (2000) Pattern Anal Appl, 3, pp. 19-30; Devijver, P., Kittler, J., (1982) Pattern Recognition: A Statistical Approach, , Prentice-Hall, New Jersey; Cheng, Y., Mean shift, mode seeking, and clustering (1995) IEEE Trans Pattern Anal Mach Intell, 17, pp. 790-799; Vijaya, P.A., Murty, M.N., Subramanian, D.K., Efficient median based clustering and classification techniques for protein sequences (2006) Pattern Anal Appl, 9, pp. 243-255; Sousa, A.V., Mendonça, A.M., Campilho, A., Aguiar, R., Miranda, C.S., Feature extraction for classification of thin-layer chromatography images (2005) Proceedings of Image Analysis and Recognition, Second International Conference, ICIAR 2005, 3656, pp. 974-981. , LNCS Springer, Toronto; Dempster, A., Laird, N., Rubin, D., Maximum likelihood from incomplete data via the em algorithm (1977) J R Stat Soc, B-39, pp. 1-38. , 1; Moré, J.J., Sorensen, D.C., Computing a trust region step (1983) SIAM J Sci Stat Comput, 4, pp. 553-572; Byrd, R.H., Schnabel, R.B., Shultz, G.A., Approximate solution of the trust region problem by minimization over two-dimensional subspaces (1988) Math Program, 40, pp. 247-263; Visa, S., Ralescu, A., Learning imbalanced and overlapping classes using fuzzy sets (2003) Workshop on Learning from Imbalanced Datasets II, , ICML, Washington DC; Sousa, A.V., Mendonça, A.M., Campilho, A.C., The class imbalance problem in TLC image classification (2006) Proceedings of Image Analysis and Recognition, Third International Conference, ICIAR 2006, 4142, pp. 513-523. , September 18-20, 2006, proceedings, Part II, Póvoa de Varzim. LNCS Springer, Portugal
Keywords: Chromatographic images; Dissimilarity representation; Nearest neighbour classifiers; Prototype selection

Hybrid chitosan membranes tested in sheep for guided tissue regeneration - Cortez, P.P.; Shirosaki, Y.; Botelho, C.M.; Simões, M.J.; Gartner, F.; Da Costa, R.M.G.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Maurício, A.C. (Key Engineering MaterialsKey Eng Mat, 2008)
Previous in vitro studies confirmed an improved cytocompatibility of chitosan-silicate hybrid membranes over chitosan membranes. The main goal of this study was to assess the in vivo histocompatibility of both membranes through subcutaneous implantations at different time periods, 1 week, 1, 2 and 3 months, using a sheep model. Chitosan membranes elicited an exuberant inflammatory response and were consequently rejected. The hybrid chitosan membranes were not rejected and the degree of inflammatory response decreased gradually until the third month of implantation. Histological evaluation also showed that these membranes can be resorbed in vivo. This study demonstrates that the incorporation of silicate into the chitosan solution improves its histocompatibility, indicating that the hybrid chitosan-silicate membranes are suitable candidates to be used in clinical applications.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Cortez, P.P.; Centro de Estudos de Ciência Animal (CECA), Instituto de Ciências e Tecnologias Agrárias e Agro-Alimentares (ICETA), Campus Agrário de Vairão, Rua P. Armando Quintas, 4485-661, Vairão, Portugal; email: pcortez@mail.icav.up.ptReferences: Nasser, N.J., Friedman, A., Friedman, M., Moor, E., Mosheiff, R., (2005) Injury, 36, p. 1460;Chandy, T., Sharma, C.P., (1990) Biomater. Artif. Cells Artif. Organs, 18, p. 1; Domard, A., Rinaudo, M., (1983) Int J Biol Macromol, 5, p. 49; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2004) Key Eng. Mat, 254-256, p. 857; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2005) Biomaterials, 26, p. 485; Ueno, H., Yamada, H., Tanaka, I., Kaba, N., Matsuura, M., Okumura, M., Kadosawa, T., Fujinaga, T., (1999) Biomaterials, 20, p. 1407
Keywords: biodegradability; Biodegradable membrane; Biodegradable membranes; chitosan; Chitosan-silicate hybrid; Guided tissue regeneration (GTR); histology; in vivo study; Membranes; Silicates; Tissue culture

The influence of the risk functional in data classification with MLPs - Silva, L.M.; Embrechts, M.; Santos, J.M.; De Sá, J.M. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
We investigate the capability of multilayer perceptrons using specific risk functionals attaining the minimum probability of error (optimal performance) achievable by the class of mappings implemented by the multilayer perceptron (MLP). For that purpose we have carried out a large set of experiments using different risk functionals and datasets. The experiments were rigorously controlled so that any performance difference could only be attributed to the different risk functional being used. Statistical analysis was also conducted in a careful way. From the several conclusions that can be drawn from our experimental results it is worth to emphasize that a risk functional based on a specially tuned exponentially weighted distance attained the best performance in a large variety of datasets. As to the issue of attaining the minimum probability of error we also carried out classification experiments using non-MLP classifiers that implement complex mappings and are known to provide the best results until this date. These experiments have provided evidence that at least in many cases, by using an adequate risk functional, it will be possible to reach the optimal performance. © Springer-Verlag Berlin Heidelberg 2008.
Conference code: 73798Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-540-87536-9_20Language of Original Document: EnglishCorrespondence Address: Silva, L. M.; INEB -Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUP, Rua Dr. Roberto Frias, 4200 - 465 Porto, Portugal; email: lmsilva@fe.up.ptReferences: Silva, L.M., Alexandre, L.A., Marques de Sá, J.: Data classification with multilayer perceptrons using a generalized error function. Neural Networks (2008) doi:10.1016/j.neunet.2008.04,004Erdogmus, D., Principe, J.C., Generalized information potential criterion for adaptive system training (2002) IEEE Transactions on Neural Networks, 13 (5), pp. 1035-1044;Erdogmus, D., Principe, J.C., An Error-Entropy Minimization Algorithm for Supervised Training of Nonlinear Adaptive Systems (2002) IEEE Transactions on Signal Processing, 50 (7), pp. 1780-1786; Santos, J.M., Alexandre, L.A., Marques de Sá, J., The Error Entropy Minimization Algorithm for Neural Network Classification (2004) Int. Conf. on Recent Advances in Soft Computing, , Nottingham, United Kingdom; Duda, R., Hart, P., Stork, D., (2001) Pattern Classification, , Wiley-Interscience, Chichester; Newman, D., Hettich, S., Blake, C., Merz, C., (1998) UCI repository of machine learning databases; Baum, E.B., Haussler, D., What size net gives valid generalization? (1990) Neural Computation, 1 (1), pp. 151-160; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Neural Networks Trained with the EEM Algorithm: Tuning the Smoothing Parameter (2005) WSEAS Transactions on Systems, 4 (4), pp. 295-300; Marques de Sá, J., (2007) Using SPSS, STATISTICA, MATLAB and R, , 2nd edn. Springer, Heidelberg; Embrechts, M.J., Szymanski, B., Sternickel, M., Introduction to Scientific Data Mining: Direct Kernel Methods and Applications (2004) Computationally Intelligent Hybrid Systems, pp. 317-363. , ch. 10, pp, Wiley Interscience, Chichester; Bennett, K.P., Embrechts, M.J., An Optimization Perspective on Kernel Partial Least Squares Regression (2003) Models and Applications. NATO Science Series, 3, pp. 227-249. , Advances in Learning Theory: Methods, 190, pp, IOS Press, Amsterdam; Suykens, J.A.K., Vandewalle, J., Least squares support vector machine classifiers (1999) Neural Processing Letters, 9 (3), pp. 293-300; Suykens, J.A.K., Gestel, T.V., Brabanter, J.D., Moor, B.D., Vandewalle, J., (2003) Least Squares Support Vector Machines, , World Scientific Pub. Co, Singapore; Keerthi, S.S., Shevade, S.K., SMO algorithm for least squares SVM formulations (2003) Neural Computation, 15, pp. 487-507; Cristianini, N., Shawe-Taylor, J., (2000) Support Vector Machines and Other KernelBased Learning Methods, , Cambridge University Press, Cambridge; Vapnik, V., (1998) Statistical Learning Theory, , Wiley-Interscience, Chichester; Schölkopf, B., Smola, A.J., (2002) Learning with Kernels, , MIT Press, Cambridge
Keywords: Backpropagation; Complex mapping; Data classification; Data sets; Electric loads; Experiments; Functionals; Minimum probability of error; MLP classifiers; Multi layer perceptron; Multi-layer perceptrons; Multilayer neural networks; Multilayers; Optimal performance; Pattern recognition systems; Probability density function; risks; Statistical analysis; Weighted distance

Jaw avascular osteonecrosis after treatment of multiple myeloma with zoledronate - Lobato, J.V.; Maurício, A.C.; Rodrigues, J.M.; Cavaleiro, M.V.; Cortez, P.P.; Xavier, L.; Botelho, C.; Hussain, N.S.; Santos, J.D. (Journal of Plastic, Reconstructive and Aesthetic SurgeryJ. Plast. Reconstr. Aesthetic Surg., 2008)
Purpose: Multiple myeloma, the second most common haematopoietic cancer, which represents the collection of plasma-cell neoplasms that invariably becomes fatal when self-renewing myeloma cells begin unrestrained proliferation. The major clinical manifestation of multiple myeloma is related to the loss of bone through osteolysis. This can lead to pathologic fractures, spinal cord compression, hypercalcaemia, and pain. It is also a major cause of morbidity and mortality in these patients, who frequently require radiation therapy, surgery and analgesic medications. Bisphosphonates are specific inhibitors of osteoclastic activity, and are currently used to prevent bone complications and to treat malignant hypercalcaemia in patients with multiple myeloma, or bone metastases from breast and prostate cancers. Hence, osteonecrosis of the mandible has been reported in three patients from Centro Hospitalar de Vila Nova de Gaia (CHVNG) with multiple myeloma treated for over 18-48 months with intravenous zoledronate, commonly prescribed for multiple myeloma therapy. Although, this report alerts clinicians about the potential complication of bone necrosis in patients receiving bisphosphonate therapy, many questions remain concerning the underlying pathogenesis of this process. Patients and methods: The medical and dental records of three patients with multiple myeloma, who were treated in CHVNG in the past 4 years, were reviewed. These three patients presented exposed bone and osteonecrosis of the mandible, and shared one common clinical feature: all of them were treated with bisphosphonate zoledronate, administered intravenously for long periods. Sequential orthopantomograms (OPGs) and histological evaluation have been analysed from the biopsies of the non healing dental extraction sites of these patients. Results: After a routine dental extraction, these patients developed avascular osteonecrosis of the mandible and secondary bone infection with Actinomyces israelii (actinomycotic osteomyelitis), with no evidence of metastatic disease evaluated by biopsy. In these three described clinical cases, surgical debridment without flap elevation, intensive antibiotherapy and the suspension of the zoledronate treatment allowed a partial recovery of the patients. The purpose of this clinical report is to point out that patients suffering from multiple myeloma can develop bone osteonecrosis induced by treatment with bisphosphonates. Research to determine the mechanism of this dental phenomenon is needed to fully validate and substantiate the possible link between bisphosphonate treatment of multiple myeloma or other cancer diseases and avascular osteonecrosis of the jaws. Until then, clinicians involved in the care of patients at risk should consider this possible complication. © 2006 British Association of Plastic, Reconstructive and Aesthetic Surgeons.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.bjps.2006.06.016PubMed ID: 18068658Language of Original Document: EnglishCorrespondence Address: Maurício, A.C.; Centro de Estudos de Ciência Animal (CECA), Instituto de Ciências, Tecnologias Agrárias e Agro-Alimentares (ICETA), Campus Agrario Vairao, Rua Padre Armando Quintas, 4485-661 Vairão, Portugal; email: ana.colette@mail.icav.up.ptChemicals/CAS: amoxicillin, 26787-78-0, 34642-77-8, 61336-70-7; cyclophosphamide, 50-18-0; cyclosporin, 79217-60-0; dexamethasone, 50-02-2; erythropoietin, 11096-26-7; thalidomide, 50-35-1; zoledronic acid, 118072-93-8, 131654-46-1, 165800-06-6, 165800-07-7; Bone Density Conservation Agents; Diphosphonates; Imidazoles; zoledronic acid, 118072-93-8References: Mundy, G.R., Bertoline, D.R., Bone destruction and hypercalcemia in plasma cell myeloma (1986) Semin Oncol, 13 (3), pp. 291-299;Belch, A.R., Bergsagel, D.E., Wilson, K., Effect of daily etidronate on the osteolysis of multiple myeloma (1991) J Clin Oncol, 9 (8), pp. 1397-1402; Kyle, R.A., Jowsey, J., Kelly, P.J., Multiple myeloma bone disease. The comparative effect of sodium fluoride and calcium carbonate or placebo (1975) N Engl J Med, 293 (26), pp. 1334-1338; Kyle, R.A., Multiple myeloma: review of 869 cases (1975) Mayo Clin Proc, 50 (1), pp. 29-40; Roodman, G.D., Pathogenesis of myeloma bone disease (2004) Blood Cells Mol Dis, 32 (2), pp. 290-292; Berenson, J.R., Myeloma bone disease (2005) Best Pract Res Clin Haematol, 18 (4), pp. 653-672; Ruggerio, S.L., Mekrotra, B., Rosenberg, T.J., Osteonecrosis of the jaws associated with the use of bisphosphonates: a review of 63 cases (2004) J Oral Maxillofac Surg, 62, pp. 527-534; Rodan, G.A., Fleisch, H.A., Bisphosphonates: mechanism of action (1996) J Clin Invest, 97 (12), pp. 2692-2696; Coleman, R.E., Metastatic bone disease: clinical features, pathophysiology and treatment strategies (2001) Cancer Treat Rev, 27 (3), pp. 165-176; Sietsema, W.K., Ebetino, F.H., Salvagno, A.M., Antiresorptive dose-response relationship across three generations of bisphosphonates (1989) Drugs Exp Clin Res, 15 (9), pp. 389-396; Schenk, R., Eggli, P., Fleisch, H., Quantitative morphometric evaluation of the inhibitory activity of new amino-bisphosphonates on bone resorption in the rat (1986) Calcif Tissue Int, 38, pp. 342-349; Jung, A., Bisaz, S., Fleisch, H., The binding of pyrophosphate and two diphosphonates by hydroxyapatite crystals (1973) Calcif Tissue Res, 11 (4), pp. 269-280; Coukell, A.J., Markham, A., Pamidronate. A review of its use in the management of osteolytic bone metastases, tumor-induced hypercalcaemia and Paget's disease of bone (1998) Drugs Aging, 12 (2), pp. 149-168; Hughes, D.E., MacDonald, B.R., Russel, R.G.G., Inhibition of osteoclast-like cell formation by bisphosphonates in long-term cultures of human bone marrow (1989) J Clin Invest, 83 (6), pp. 1930-1935; Hughes, D.E., Wright, K.R., Uy, H.L., Bisphosphonates promote apoptosis in murine osteoclasts in vitro and in vivo (1995) J Bone Miner Res, 10 (10), pp. 1478-1487; Murakami, H., Takahashi, N., Sasaki, T., A possible mechanism of the specific action of bisphosphonates on osteoclasts: tiludronate preferentially affects polarized osteoclasts having ruffled borders (1995) Bone, 17 (2), pp. 137-144; Sahni, M., Guenther, H.L., Fleisch, H., Bisphosphonates act on rat bone resorption through the mediation of osteoblasts (1993) J Clin Invest, 91 (5), pp. 2004-2011; Fleisch, H., Bisphosphonates: mechanisms of action (1998) Endocr Rev, 19 (1), pp. 80-100; Shinoda, H., Adamek, G., Félix, R., Structure-activity relationships of various bisphosphonates (1983) Calcif Tissue Int, 35 (1), pp. 87-99; Pereira, J., Mancini, I., Walker, P., The role of bisphosphonates in malignant bone pain: a review (1998) J Palliat Care, 14 (2), pp. 25-36; Purohit, O.P., Radstone, C.R., Anthony, C., A randomized double-blind comparison of intravenous pamidronate and clodronate in the hypercalcemia of malignancy (1995) Br J Cancer, 72 (5), pp. 1289-1293; Hillner, B.E., Ingle, J.N., Chlebowski, R.T., American Society of Clinical Oncology 2003 update on the role of bisphosphonates and bone health issues in women with breast cancer (2003) J Clin Oncol, 21 (21), pp. 4042-4057. , [Erratum in J Clin Oncol 2004;22(7):1351]; Hillner, B.E., Ingle, J.N., Berenson, J.R., American Society of Clinical Oncology guideline on the role of bisphosphonates in breast cancer. American Society of Clinical Oncology Bisphosphonates Expert Panel (2000) J Clin Oncol, 18 (6), pp. 1378-1391; Lacerna, L., Hohneker, J., Zoledronic acid for the treatment of bone metastases in patients with breast cancer and other solid tumours (2003) Semin Oncol, 30 (5 SUPPL. 16), pp. 150-160; Lipton, A., Costa, L., Ali, S., Use of markers of bone turnover for monitoring bone metastases and the response to therapy (2001) Semin Oncol, 28 (4 SUPPL. 11), pp. 54-59; Brincker, H., Westin, J., Abildgaard, N., Failure of oral pamidronate to reduce skeletal morbidity in multiple myeloma: a double-blind placebo-controlled trial. Danish-Swedish Co-operative Study Group (1998) Br J Haematol, 101 (2), pp. 3280-3286; Berenson, J.R., Lichtenstein, A., Porter, L., Long-term pamidronate treatment of advanced multiple myeloma patients reduces skeletal events. Myeloma Aredia Study Group (1998) J Clin Oncol, 16 (7), pp. 593-602; Berenson, J.R., Vescio, R.A., Lee, S.R., Phase I dose-ranging trial of monthly infusions of zoledronic acid for the treatment of osteolytic bone metastases (2001) Clin Cancer Res, 7 (3), pp. 478-485; Van Poznak, C.H., The use of bisphosphonates in patients with breast cancer (2002) Cancer Control, 9 (6), pp. 480-489; Marx, R.E., Pamidronate (Aredia) and zoledronate (Zometa) induced avascular necrosis of the jaws: a growing epidemic (2003) J Oral Maxillofac Surg, 61 (9), pp. 1115-1117; Vannucchi, A.M., Ficarra, G., Antonioli, E., Osteonecrosis of the jaw associated with zoledronate therapy in patient with multiple myeloma (2005) Br J Haematol, 128 (6), pp. 738-739; Wang, J., Goodger, N.M., Pogrel, M.A., Osteonecrosis of the jaws associated with cancer chemotherapy (2003) J Oral Maxillofac Surg, 61 (9), pp. 1104-1107; Purcell, P.M., Boyd, I.W., Bisphosphonates and osteonecrosis of the jaw (2005) Med J Aust, 182 (8), pp. 417-418; Carter, G., Goss, A.N., Doecke, C., Bisphosphonates and avascular necrosis of the jaw: a possible association (2005) Med J Aust, 182 (8), pp. 413-415; Durie, B., Katz, M., Crowley, J., Osteonecrosis of the jaw and bisphosphonates (2005) N Engl J Med, 353, pp. 99-102; Migliorati, C.A., Bisphosphonates and oral cavity avascular bone necrosis (2003) J Clin Oncol, 21 (22), pp. 4253-4254; Robinson, N.A., Yeo, J.F., Bisphosphonates - a word of caution (2004) Ann Acad Med Singapore, 33 (4), pp. 48-49; Starck, W.J., Epker, B.N., Failure of osseointegrated dental implants after diphosphonate therapy for osteoporosis: a case report (1995) Int J Oral Maxillofac Implants, 10 (1), pp. 74-78; Melo, M., Obeid, G., Osteonecrosis of the maxilla in a patient with a history of bisphosphonate therapy (2005) J Can Dent Assoc, 71 (2), pp. 111-113
Keywords: Actinomyces israelii; adult; aged; amoxicillin; antibiotic therapy; article; avascular necrosis; Avascular osteonecrosis; biopsy; Bisphosphonates; Bone Density Conservation Agents; case report; clinical feature; cyclophosphamide; cyclosporin; dexamethasone; Diphosphonates; drug induced disease; drug inhibition; drug withdrawal; erythropoietin; Female; histology; human; Humans; hypercalcemia; Imidazoles; Jaw; jaw avascular osteonecrosis; male; Mandibular Diseases; morbidity; mortality; Multiple myeloma; osteolysis; Osteonecrosis; pain; panoramic radiography; pathologic fracture; priority journal; Radiography, Panoramic; risk assessment; spinal cord compression; thalidomide; tooth extraction; zoledronic acid

Joint detection of the carotid boundaries in longitudinal B-mode images - Rocha, R.; Campilho, A.; Silva, J. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
This paper proposes a new approach for the automatic segmentation of the carotid adventitia in longitudinal B-scans, with and without the presence of plaque. The top and bottom adventitia contours are jointly detected with a 3D dynamic programing scheme that searches for the best pair of boundaries according to a specified fuzzy cost function. Some discriminating features of the adventitia in B-mode images are used to reduce the attraction by other edges. The final contours are filtered with a smoothing spline fitting. The proposed approach was quantitatively evaluated in a set of 38 images. In order to avoid high correlation of the results, a maximum of two images was selected from each patient. The carotid boundaries manually traced by a medical expert were used as the ground truth. Several statistics show that the proposed algorithm gives good results in most of the cases, including many poor quality images. Examples of the detected contours are presented and compared with the ground truth. © 2008 Springer-Verlag Berlin Heidelberg.
Conference code: 72695Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-540-69812-8_75Language of Original Document: EnglishCorrespondence Address: Rocha, R.; INEB - Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUP, 4200-465 Porto, PortugalReferences: Gee, A., Prager, R., Treece, G., Berman, L., Engineering a freehand 3D ultrasound system (2003) Pattern Recogn. Lett, 24 (4-5), pp. 757-777;Sonka, M., Liang, W., Stefancik, R., Stolpen, A., Handbook of Medical Imaging: Medical Image Processing and Analysis (2000) SPIE, 2; Gustavsson, T., Liang, Q., Wendelhag, I., Wikstrand, J., A dynamic programming procedure for automated ultrasonic measurement of the carotid artery (1994) Computers in Cardiology, 297-300; Liang, Q., Wendelhag, I., Wikstrand, J., Gustavsson, T., A multiscale dynamic programming procedure for boundary detection in ultrasound artery images (2000) IEEE Trans. Med. Imag, 19 (2), pp. 127-142; Cheng, D., Jiang, X., Schmidt-Trucksass, A., Cheng, K., Automatic intima-media thickness measurement of carotid artery wall in B-mode sonographic images (2006) IEEE International Symposium on Biomedical Imaging (ISBI, pp. 912-915. , IEEE, Los Alamitos; Halenka, M., (1999) Noninvasive measurement of early atherosclerosis by high-resolution B-mode ultrasonography, 142, pp. 7-12. , Acta- Universitatis Palackianae Olomucensis Facultatis Medicae; Yu, Y., Acton, S., Speckle reducing anisotropic diffusion (2002) IEEE Trans. Image Processing, 11 (11), pp. 1260-1270; Yu, Y., Acton, S., Edge detection in ultrasound imagery using the instantaneous coefficient of variation (2004) IEEE Trans. Image Processing, 13 (12), pp. 1640-1655; Canny, J., A computational approach to edge detection (1986) IEEE Trans. Pattern Analysis and Machine Intelligence, 8 (6), pp. 679-698; Guo, Z., Hall, R.W., Parallel thinning with two-subiteration algorithms (1989) Commun. ACM, 32 (3), pp. 359-373; Black, M.J., Sapiro, G., Marimont, D.H., Heeger, D., Robust anisotropic diffusion (1998) IEEE Trans. Image Processing, 7 (3), pp. 421-432; Tauber, C., (2005) Filtrage anisotrope robuste et segmentation par B-spline snake: Application aux images échographiques, , PhD thesis, Institut National Polytechnique de Toulouse, Toulouse Février; de Boor, C., (1978) A Practical Guide to Splines, , Springer, Heidelberg
Keywords: Automatic segmentations; B-Mode imaging; Edge detection; Fuzzy costs; Ground truth; Heidelberg (CO); Image analysis; Image enhancement; Imaging techniques; International conferences; Joint detection (JD); Medical experts; New approaches; Regression analysis; Smoothing splines

LEGClust - A clustering algorithm based on layered entropic subgraphs - Santos, J.M.; De Sá, J.M.; Alexandre, L.A. (IEEE Transactions on Pattern Analysis and Machine IntelligenceIEEE Trans Pattern Anal Mach Intell, 2008)
Hierarchical clustering is a stepwise clustering method usually based on proximity measures between objects or sets of objects from a given data set. The most common proximity measures are distance measures. The derived proximity matrices can be used to build graphs, which provide the basic structure for some clustering methods. We present here a new proximity matrix based on an entropic measure and also a clustering algorithm (LEGClust) that builds layers of subgraphs based on this matrix, and uses them and a hierarchical agglomerative clustering technique to form the clusters. Our approach capitalizes on both a graph structure and a hierarchical construction. Moreover, by using entropy as a proximity measure we are able, with no assumption about the cluster shapes, to capture the local structure of the data, forcing the clustering method to reflect this structure. We present several experiments on artificial and real data sets that provide evidence on the superior performance of this new algorithm when compared with competing ones. © 2007 IEEE.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: ITPIDdoi: 10.1109/TPAMI.2007.1142Language of Original Document: EnglishCorrespondence Address: Santos, J.M.; Department of Mathematics, ISEP - Polytechnic School of Engineering, R. Dr. A. Bernardino de Almeida 431, 4200-072 Porto, Portugal; email: jms@isep.ipp.ptReferences: Jain, A.K., Dubes, R.C., (1988) Algorithms for Clustering Data, , Prentice Hall International;Jain, A.K., Murty, M.N., Flynn, P.J., Data clustering: A review (1999) ACM Computing Surveys, 31 (3), pp. 264-323; Jain, A., Topchy, A., Law, M., Buhmann, J., Landscape of clustering algorithms (2004) 17th International Conference on Pattern Recognition, 1, pp. 260-263; Berkhin, P., (2002) Survey of clustering data mining techniques, , Accrue Software, San Jose, CA, Tech. Rep; Guha, S., Rastogi, R., Shim, K., CURE: An efficient clustering algorithm for large databases (1998) ACM SIGMOD International Conference on Management of Data, pp. 73-84; Guha, S., Rastogi, R., Shim, K., ROCK: A robust clustering algorithm for categorical attributes (2000) Information Systems, 25 (5), pp. 345-366; Kaufman, L., Rousseeuw, P., (1990) Finding Groups in Data: An Introduction to Cluster Analysis, , New York, NY: John Wiley and Sons; Zhang, T., Ramakrishnan, R., Livny, M., BIRCH: An efficient clustering method for very large databases (1996) ACM SIGMOD Workshop on Research Issues on Data Mining and Knowledge Discovery, pp. 103-114. , Montreal, Canada; Zhang, T., Ramakrishnan, R., Livny, M., BIRCH: A new data clustering algorithm and its applications (1997) Data Mining and Knowledge Discovery, 1 (2), pp. 141-182; Karypis, G., Han, E.-H.S., Kumar, V., Chameleon: Hierarchical clustering using dynamic modeling (1999) IEEE Computer, 32 (8), pp. 68-75; Kamvar, S.D., Klein, D., Manning, C.D., Interpreting and extending classical agglomerative clustering algorithms using a model-based approach (2002) Proceedings of the Nineteenth International Conference on Machine Learning, pp. 283-290. , San Francisco, CA, USA: Morgan Kaufmann Publishers Inc; Johnson, E.L., Mehrotra, A., Nemhauser, G.L., Min-cut clustering (1993) Mathematical Programming, 62, pp. 133-151; Matula, D., Cluster analysis via graph theoretic techniques (1970) Proc. Luisiana Conference on Combinatorics, Graph Theory and Computing, pp. 199-212. , R.C.Mullin, K.B.Reid, and D.P.Roselle, Eds. University of Manitoba, Winnipeg; Matula, D., k-components, clusters and slicings in graphs (1972) SIAM J. Appl. Math, 22 (3), pp. 459-480; Hartuv, E., Schmitt, A., Lange, J., Meier-Ewert, S., Lehrachs, H., Shamir, R., An algorithm for clustering cDNAs for gene expression analysis (1999) RECOMB, pp. 188-197; Hartuv, E., Shamir, R., A clustering algorithm based on graph connectivity (2000) Information Processing Letters, 76 (4-6), pp. 175-181; Wu, Z., Leahy, R., An optimal graph theoretic approach to data clustering: Theory and its application to image segmentation (1993) IEEE Transactions on Pattern Analysis and Machine Learning, 15 (11), pp. 1101-1113; G. Karypis and V. Kumar, Multilevel algorithms for multi-constraint graph partitioning, University of Minnesota, Department of Computer Science/Army HPC Research Center, Minneapolis, Tech. Rep. 98-019, May 1998Fiedler, M., A property of eigenvectors of nonnegative symmetric matrices and its application to graph theory (1975) Czechoslovak Mathematical Journal, 25 (100), pp. 619-633; Chung, F.R.K., (1997) Spectral Graph Theory, (92). , Providence, RI: American Mathematical Society; Shi, J., Malik, J., Normalized cuts and image segmentation (2000) IEEE Transactions on Pattern Analysis and Machine Intelligence, 22 (8), pp. 888-905; Kannan, R., Vempala, S., Vetta, A., On clusterings: Good, bad, and spectral (2000) Proceedings of the 41st Annual Symposium on the Foundation of Computer Science, pp. 367-380; Ding, C., He, X., Zha, H., Gu, M., Simon, H., A min-max cut algorithm for graph partitioning and data clustering (2001) International Conference on Data Mining, pp. 107-114; Ng, A.Y., Jordan, M.I., Weiss, Y., On spectral clustering: Analysis and an algorithm (2001) Advances in Neural Information Processing Systems, 14; Meila, M., Shi, J., A random walks view of spectral segmentation (2001) Eighth International Workshop on Artificial Intelligence and Statistics; Verma, D., Meila, M., (2003) A comparison of spectral clustering algorithms, , Washington University, Tech. Rep. UW-CSE-03-05-01; Ester, M., Kriegel, H.-P., Sander, J., Xu, X., A density-based algorithm for discovering clusters in large spatial databases with noise (1996) 2nd International Conference on Knowledge Discovery and Data Mining, pp. 226-231. , A. Press, Ed; Fukunaga, K., Hostetler, L.D., The estimation of the gradient of a density function, with applications in pattern recognition (1975) IEEE Trans. in Information Theory, 21, pp. 32-40; Cheng, Y., Mean shift, mode seeking, and clustering (1995) IEEE Trans. on Pattern Analysis and Machine Intelligence, 17 (8), pp. 790-799; Comaniciu, D., Meer, P., Mean shift analysis and applications (1999) IEEE International Conference on Computer Vision, pp. 1197-1203; Comaniciu, D., Meer, P., Mean shift: A robust approach toward feature space analisys (2002) IEEE Trans. on Pattern Analysis and Machine Intelligence, 24 (5), pp. 603-619; Fischer, B., Zöller, T., Buhmann, J.M., Path based pairwise data clustering with application to texture segmentation (2001) LNCS - Proceed. of International Workshop on Energy Minimization Methods in Computer Vision and Pattern Recognition, 2134, pp. 235-250; Fischer, B., Buhmann, J.M., Path-based clustering for grouping of smooth curves and texture segmentation (2003) IEEE Transactions on Pattern Analysis and Machine Intelligence, 25 (4), pp. 513-518; Shannon, C., A mathematical theory of communication (1948) Bell System Technical Journal, 27, pp. 379-423,623-656; Renyi, A., Some fundamental questions of information theory (1976) Selected Papers of Alfred Renyi, 2, pp. 526-552; Parzen, E., On the estimation of a probability density function and mode (1962) Annals of Mathematical Statistics, 33, pp. 1065-1076; Xu, D., Príncipe, J., Training mlps layer-by-layer with the information potential (1999) Intl. Joint Conf. on Neural Networks, pp. 1716-1720; H. Li, K. Zhang, and T. Jiang, Minimum entropy clustering and applications to gene expression analysis, in IEEE Computational Systems Bioinformatics Conference, IEEE, Ed., 2004, pp. 142-151Hero, A.O., Ma, B., Michel, O.J., Gorman, J., Applications of entropic spanning graphs (2002) IEEE Signal Processing Magazine, 19 (5), pp. 85-95; Cheng, C.H., Fu, A.W., Zhang, Y., Entropy-based subspace clustering for mining numerical data (1999) International Conference on Knowledge Discovery and Data Mining; Jenssen, R., Hild, I., Erdogmus, K.E.D., Príncipe, J., Eltoft, T., Clustering using renyi's entropy (2003) Proceedings of the International Joint Conference on Neural Networks, pp. 523-528; Gokcay, E., Príncipe, J.C., Information theoretic clustering (2002) IEEE Transactions on Pattern Analysis and Machine Learning, 24 (2), pp. 158-171; Lee, Y., Choi, S., Minimum entropy, k-means, spectral clustering (2004) IEEE International Joint Conference on Neural Networks, 1, pp. 117-122; Lee, Y., Maximum within-cluster association (2005) Pattern Recognition Letters, 26 (10), pp. 1412-1422. , July; J. M. Santos and J. Marques de Sá, Human clustering on bi-dimensional data: An assessment, INEB - Instituto de Engenharia Biomédica, Porto, Portugal, Technical Report 1, October 2005. [Online]. Available: http://www.fe.up.pt/~nnig/papers/ JMS_TechReport2005_1.pdfSilverman, B.W., (1986) Density Estimation for Statistics and Data Analisys, 26. , Chapman & Hall; Bowman, A.W., Azzalini, A., (1997) Applied Smooting Techniques for Data Analysis, , London: Oxford University Press; Jenssen, R., Eltoft, T., Príncipe, J., Information theoretic spectral clustering (2004) Proceedings of the International Joint Conference on Neural Networks, pp. 111-116; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Neural Networks Trained with the EEM Algorithm: Tuning the Smoothing Parameter (2005) 6th WSEAS Int. Conf. on Neural Networks; Proença, H., Alexandre, L.A., UBIRIS: A noisy iris image database (2005) Proceed. of ICIAP 2005 - Intern. Confer. on Image Analysis and Processing, 1, pp. 970-977; (2000), http:// genome-www.stanford.edu/nci60, Stanford NCI60 cancer microarray projectBlake, C., Keogh, E., Merz, C., (1998) UCI repository of machine learning Databases, , http://www.ics.uci.edu/~mlearn/MLRepository.html; Forina, M., Armanino, C., Eigenvector projection and simplified nonlinear mapping of fatty acid content of italian olive oils (1981) Ann. Chim. (Rome), 72, pp. 127-155; G. Karypis, Cluto: Software package for clustering high-dimensional datasets, November 2003, version 2.1.1Karypis, G., (2003) Cluto: A Clustering Toolkit, , University of Minnesota, Department of Computer Science, Minneapolis, MN 55455, November; Sanguinetti, G., Laidler, J., Lawrence, N.D., Automatic determination of the number of clusters using spectral algorithms (2005) International Workshop on Machine Learning for Signal Processing, pp. 55-60; Xu, X., Dbscan, , http://ifsc.ualr.edu/xwxu, Online, Available; Duin, R.P., Dutch handwritten numerals, , http://www.ph.tn.tudelft.nl/~duin; Hubert, L., Arabie, P., Comparing partitions (1985) Journal of Classification, 2 (1), pp. 193-218; Porter, M.F., An algorithm for suffix stripping (1980) Program, 14 (3), pp. 130-137; Hastie, T., Tibshirani, R., Friedman, J., (2001) The Elements of Statistical Learning, , Springer
Keywords: algorithm; Algorithms; article; artificial intelligence; automated pattern recognition; Cluster Analysis; Clustering; Clustering algorithms; computer assisted diagnosis; Distance measurement; Entropic subgraphs; entropy; Graph theory; Graphs; Hierarchical clustering; Hierarchical systems; Image enhancement; Image Interpretation, Computer-Assisted; Imaging, Three-Dimensional; methodology; Pattern Recognition, Automated; reproducibility; Reproducibility of Results; sensitivity and specificity; three dimensional imaging

Minimizing the imbalance problem in chromatographic profile classification with one-class classifiers - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
This paper presents a new classification approach to deal with class imbalance in TLC patterns, which is due to the huge difference between the number of normal and pathological cases as a consequence of the rarity of LSD diseases. The proposed architecture is formed by two decision stages: the first is implemented by a one-class classifier aiming at recognizing most of the normal samples; the second stage is a hierarchical classifier which deals with the remaining outliers that are expected to contain the pathological cases and a small percentage of normal samples. We have also evaluated this architecture by a forest of classifiers, using the majority voting as a rule to generate the final classification. The results that were obtained proved that this approach is able to overcome some of the difficulties associated with class imbalance. © 2008 Springer-Verlag Berlin Heidelberg.
Conference code: 72695Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-540-69812-8_41Language of Original Document: EnglishCorrespondence Address: Sousa, A. V.; Instituto de Engenharia Biomédica, Rua Roberto Frias, 4200-465 Porto, Portugal; email: ats@isep.ipp.ptReferences: Keir, G., Winchester, B.G., Clayton, P., Carbohydrate-deficient Glycoprotein Syndromes: Inborn Errors of Protein Glycosylate (1999) Ann. Clin. Biochem, 36 (PART 1), pp. 20-36;Durand, G., Seta, N., Protein Glycosylation and Diseases: Blood and Urinary Oligosaccharides as Markers for Diagnosis and Therapeutic Monitoring (2000) Clin. Chem, 46, pp. 795-805; Scriver, S.R., Beaudet, A.L., Sly, W.S., Valle, D., (2001) The Metabolic Bases of Inherited Disease, 3. , MCGraw-Hill, New-York; Friedman, R.B., Williams, M.A., Moser, H.W., Kolodny, E.H., Improved Thin-Layer Chromatographic Method in the Diagnosis of Mannosidosis (1978) Clinical Chemistry, 24, pp. 1576-1577; Kurczynski, T.W., Kendzierski, K.S., Sewell, A.C., Kuczynski, T.W., Urinary Oligosaccharides in Pregnant or Lactating Women: Pitfall in Screening (1993) Clin. Chem, 39, pp. 2346-2347; Sewell, A.C., Urinary Oligosaccharides. Techniques in Diagnostic Human (1991) Biochemical Genetics, 219-231; Duvdevani-Bar, S., Edelman, S., Visual Recognition and Categorization on the Basis of Similarities to Multiple Class Prototypes (1999) Int. J. Comput. Vision, 33, pp. 201-228; Pekalska, E., Duin, R.P.W., Dissimilarity Representations Allow for Building Good Classifiers (2002) Pattern Recogn. Lett, 23, pp. 943-956; Goldstone, R.L., Son, J.Y., Similarity (2005) Cambridge Handbook of Thinking and Reasoning, pp. 13-36. , Holyoak, K, Morrison, R, eds, Cambridge University Press, Cambridge; Pekalska, E., Duin, R.P.W., (2005) The Dissimilarity Representation for Pattern Recognition -Fundations and Applications, 64. , World Scientific Publishing, Singapore; Lavine, B.K., Clustering and Classification of Analytical Data (2000) Encyclopedia of Analytical Chemistry: Instrumentation and Applications, pp. 9689-9710. , Meyers, R.A, ed, John Wiley & Sons, Chichester; Kubat, M., Holte, R., Matwin, S.: Learning when Negative Examples Abound. In: van Someren, M., Widmer, G. (eds.) ECML 1997. LNCS, 1224, pp. 146-153. Springer, Heidelberg (1997)Skurichina, M., Raudys, S., Duin, R.P.W., K-Nearest Neighbors Directed Noise Injection in Multilayer Perceptron Training (2000) IEEE Transactions on Neural Networks, 11; Chawla, N.V., Japkowicz, N., Kolcz, A., Editorial: Special Issue: Learning from Imbalanced Data Sets (2004) Sigkdd Explorations, 6, pp. 1-6; Tax, D.M.J., (2001) One-class Classification; Concept-learning in the Absence of Counter-examples, , Ph.D. thesis: Delft University of Technology; Sousa, A.V., Mendonça, A.M., Campilho, A., Chromatographic Pattern Classification (2007) IEEE Trans. on Biomedical Engineering, , doi:10.1109/TBME.2008.919852; Paclik, P., Duin, R.P.W., Dissimilarity-based Classification of Spectra: Computational Issues (2003) Real-Time Imaging, 9, pp. 237-244; Paclik, P., Duin, R.P.W., Classifying Spectral Data using Relational Representation (2003) Proc. of Spectral Imaging Workshop, , Graz, Austria; Sousa, A.V., Mendonça, A.M., Campilho, A., Dissimilarity-based Classification of Chromatographic Profiles (2007) Pattern Analysis and Applications, , doi:10.1007/sl0044-008-0113-2; Pekalska, E., Paclik, P., Duin, R.P.W., A Generalized Kernel Approach to Dissimilarity-based Classifcation (2001) Journal of Machine Learning Research, 2, pp. 175-211; Ripley, B.D., (2004) Pattern Recognition and Neural Networks, , Cambridge University Press, Cambridge; Visa, S., Ralescu, A., Learning Imbalanced and Overlapping Classes Using Fuzzy Sets (2003) Workshop on Learning from Imbalanced Datasets II, ICML, , Washington DC
Keywords: Class imbalances; Classification (of information); Classification approach; Classifiers; Heidelberg (CO); Hierarchical classifiers; Image analysis; Imaging techniques; Imbalance problems; International conferences; Learning systems; Majority voting; Pathological cases

Molecular epidemiology of pseudomonas aeruginosa clinical isolates from Portuguese Central Hospital - Fonseca, A.P.; Correia, P.; Extremina, C.I.; Sousa, J.C.; Tenreiro, R.; Barros, H. (Folia MicrobiologicaFolia Microbiol., 2008)
The relatedness between clinical isolates of P. aeruginosa obtained from patients during their stay in a Portuguese Central Hospital was evaluated. Genotypic fingerprinting (M13-PCR), phenotypic methods (biotyping and antibiotyping) and epidemiological information (spatial and temporal links) were used to evaluate the relatedness between 88 clinical isolates (68 patients), selected randomly out of 189. Sixty-two M13 types were found, 12 of them containing isolates from more than one patient. Thirty-four antibiotypes were found, as well as a significant association (p < 0.05) between epidemic isolates and multiresistance patterns. The nosocomial transmission of P. aeruginosa strains may be limited since M13 typing demonstrated a high degree of diversity among all the isolates, suggesting the occurrence of mainly independent infectious episodes. The results show the possible occurrence of cross-acquisition, cross-colonization and cross-infection and suggest an epidemic population structure for P. aeruginosa in this hospital.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: FOMIAdoi: 10.1007/s12223-008-0086-yLanguage of Original Document: EnglishCorrespondence Address: Fonseca, A. P.Rua Roberto Frias s/n, 4200-465 Porto, Portugal; email: apfonseca08@sapo.ptChemicals/CAS: DNA, BacterialReferences: Bergmans, D., Bonten, M., van tiel, F., Gaillard, C., London, N., van der Geest, S., de Leeuw, P., Stobbrringh, E., Value of phenotyping methods as an initial screening of Pseudomonas aeruginosa in epidemiologic studies (1997) Infection, 25, pp. 350-354;Bertrand, X., Thouverez, M., Talon, D., Boillot, A., Capellier, G., Floriot, C., Helias, J.P., Endemicity, molecular diversity and colonization routes of Pseudomonas aeruginosa in intensive care units (2001) Intens.Care Med., 27, pp. 1263-1268; Brízio, A., Silva, A., Canas, E., Ferreira, T., Lito, L.M., Cristino, J.M., Salgado, M.J., Duarte, A., Spread of ln58 containing bla VIM-2 among Pseudomonas aeruginosa (2006) Clin.Microbiol.Infect.Dis., 12 (SUPPL. 4), p. 931; Brízio, A., Vasco, S., Gonçalves, A.R., Lito, L.M., Cristino, J.M., Salgado, M.J., Duarte, A., Survey of extended-spectrum β-lactamases in Escherichia coli isolates from a Portuguese hospital and characterisation of a novel class 1 integron (In60A) carrying the blaCTX-M-9 gene (2006) Internat.J.Antimicrob.Agents, 28, pp. 320-324; Buchholz, P., Richter, M., Fiedler, G., Halle, E., Epidemiological fingerprinting of multiresistant strains of Pseudomonas aeruginosa isolated from patients of intensive care units of the Charité Hospital, Berlin (1995) Med.Microbiol.Lett., 4, pp. 7-13; Černohorská, L., Votava, M., Antibiotic synergy against biofilm-forming Pseudomonas aeruginosa (2008) Folia Microbiol, 53, pp. 57-61; Elaichouni, A., Verschraegen, G., Claeys, G., Devleeschouwer, M., Godard, C., Vaneechoutte, M., Pseudomonas aeruginosa serotype O12 outbreak studied by arbitrary primer PCR (1994) J.Clin.Microbiol., 32, pp. 666-671; Fonseca, A.P., Correia, P., Fonseca, A.F., Tenreiro, R., Sousa, J.C., Polyphasic approach to the characterization of Pseudomonas aeruginosa isolates from a Portuguese Central Hospital (2004) Clin.Microbiol.Infect., 10 (SUPPL. 3), p. 1113; Fonseca, A.P., Correia, P., Sousa, J.C., Tenreiro, R., Association patterns of Pseudomonas aeruginosa clinical isolates as revealed by virulence traits, antibiotic resistance, serotype and genotype (2007) FEMS Immunol.Med.Microbiol., 51, pp. 505-516; Grundmann, H., Kropec, A., Hartung, D., Berner, R., Daschner, F., Pseudomonas aeruginosa in a neonatal intensive care unit: Reservoirs and ecology of the nosocomial pathogen (1993) J.Infect.Dis., 168, pp. 943-947; Grundmann, H.J., Towner, K.J., Dijkshoorn, L., Gerner-smidt, P., Maher, M., Seifert, H., Vaneechoutte, M., Multicenter study using standardized protocols and reagents for evaluation of reproducibility of PCR-based fingerprinting of Acinetobacter spp (1997) J.Clin.Microbiol., 35, pp. 3071-3077; Hoštacká, A., Čižnár, I., Slobodníková, L., Kotulová, D., Clinical Pseudomonas aeruginosa: Potential factors of pathogenicity and resistance to antimicrobials (2006) Folia Microbiol, 51, pp. 633-638; Hunter, P.R., Gaston, M.M., Numerical index of the discriminatory ability of typing systems: An application of Simpson's index of diversity (1989) J.Clin.Microbiol., 26, pp. 2465-2466; Huston, W.M., Potter, A.J., Jennings, M.P., Rello, J., Hauser, A.R., McEwan, A.G., Survey of ferroxidase expression and siderophore production in clinical isolates of Pseudomonas aeruginosa (2004) J.Clin.Microbiol., 42, pp. 2806-2809; Jalaluddin, S., Devaster, J.-M., Scheen, R., Gerard, M., Butzler, J.-P., Molecular epidemiological study of nosocomial Enterobacter aerogenes isolates in a Belgian hospital (1998) J.Clin.Microbiol., 36, pp. 1846-1852; Juretschko, S., Labombardi, V.J., Lerner, S.A., Schreckenberger, P.C., Pseudomonas AST Study Group: Accuracies of β-lactam susceptibility test results for Pseudomonas aeruginosa with four automated systems (BD Phoenix, MicroScan WalkAway, Vitek, and Vitek 2) (2007) J.Clin.Microbiol., 45, pp. 1339-1342; King, E.O., Ward, M.K., Raney, D.E., Two simple media for the demonstration of pyocyanin and fluorescein (1954) J.Lab.Clin.Med., 44, pp. 301-307; Kiska, D.L., Gilligan, P.H., Pseudomonas and Burkholderia (1999) Manual of Clinical Microbiology, pp. 517-525. , in P.R.Murray,E.J.Baron,M.A.Pfaller,F.C.Tenover,R.H.Yolken(Eds) 7th ed. American Society for Microbiology,Washington (DC); Morales, G., Wiehlmann, L., Gudowius, P., van Delden, C., Tümmler, B., Martínez, J.L., Rojo, F., Structure of Pseudomonas aeruginosa populations analyzed by single nucleotide polymorphism and pulsed-field gel electrophoresis genotyping (2004) J.Bacteriol., 186, pp. 4228-4237; Nogueira, J.A., (1995) Pseudomonas Aeruginosa - Agente Nosocomial, , (In Portuguese) PhD Thesis. Faculdade de Medicina, Universidade do Porto, Porto (Portugal); Olive, P.B.D., Principles and applications of methods for DNA-based typing of microbial organisms (1999) J.Clin.Microbiol., 37, pp. 1661-1669; Pirnay, J.P., de Vos, D., Cochez, C., Bilocq, F., Vanderkelen, A., Zizi, M., Ghysels, B., Cornelis, P., Pseudomonas aeruginosa displays an epidemic population structure (2002) Environ.Microbiol., 4, pp. 898-911; Pirnay, J.P., Matthijs, S., Colak, H., Chablain, P., Bilocq, F., Van eldere, J., de Vos, D., Cornelis, P., Global Pseudomonas aeruginosa biodiversity as reflected in a Belgian river (2005) Environ.Microbiol., 7, pp. 969-980; Speijer, H., Savelkoulp, P.H.M., Bonten, M.J., Stobberingh, E.E., Tjhie, J.H.T., Application of different genotyping methods for Pseudomonas aeruginosa in a setting of endemicity in an intensive care unit (1999) J.Clin.Microbiol., 37, pp. 3654-3661; Tenover, F., Arbeit, R.D., Goering, R.V., Mickelsen, P.A., Murray, B.E., Persing, D.H., Swaminathan, B., Interpreting chromosomal DNA restriction patterns produced by pulsed-field gel electrophoresis: Criteria for bacterial strain typing (1995) J.Clin. Microbiol., 33, pp. 2233-2239; Wiehlmann, L., Wagner, G., Cramer, N., Siebert, B., Gudowius, P., Morales, G., Köhler, T., Tümmler, B., Population structure of Pseudomonas aeruginosa (2007) Proc.Nat.Acad.Sci.USA, 104, pp. 8101-8106
Keywords: antibiotic resistance; article; bacterial DNA; cross infection; disease transmission; DNA, Bacterial; Drug Resistance, Microbial; Electrophoresis, Gel, Pulsed-Field; epidemiology; genetics; genotype; Hospitals, Teaching; human; Humans; isolation and purification; microbiology; polymerase chain reaction; Portugal; Pseudomonas aeruginosa; Pseudomonas infection; Pseudomonas Infections; pulsed field gel electrophoresis; Sampling Studies; statistics; teaching hospital

Nanocrystalline diamond as a coating for joint implants: Cytotoxicity and biocompatibility assessment - Amaral, M.; Gomes, P.S.; Lopes, M.A.; Santos, J.D.; Silva, R.F.; Fernandes, M.H. (Journal of NanomaterialsJ. Nanomater., 2008)
Nanocrystalline diamond (NCD) coatings combine a very low surface roughness with the outstanding diamond properties, such as superlative hardness, low self-friction coefficient, high wear and corrosion resistance, and biotolerance, which are ideal features for applications in medicine (knee and hip replacement) and surgical tools. The present work presents a comprehensive study of the cytotoxicity and biocompatibility of NCD films grown by hot-filament chemical vapour deposition (HFCVD) technique, aiming such future applications. Cytotoxicity was evaluated in vitro by seeding human gingival fibroblasts on the NCD surface for 14 days, while specific biocompatibility was assessed on samples seeded with human bone marrow-derived osteoblasts during 21 days. The NCD coatings proved to be noncytotoxic in the preliminary human gingival fibroblast cell cultures, as denoted by a notable sequence of cell attachment, spreading, and proliferation events. In the specific biocompatibility assay envisaging bone tissue applications, NCD coatings induced human osteoblast proliferation and the stimulation of differentiation markers, compared to standard polystyrene tissue culture plates. Copyright © 2008.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusArt. No.: 894352doi: 10.1155/2008/894352Language of Original Document: EnglishCorrespondence Address: Silva, R. F.; Departamento de Engenharia Cerâmica e Vidro, Centro de Investigação em Materiais Cerâmicos e Compósitos (CICECO), Universidade de Aveiro, 3810-193 Aveiro, Portugal; email: rsilva@ua.ptReferences: Grabarczyk, J., Batory, D., Louda, P., Couvrat, P., Kotela, I., Bakowicz Mitura, K., Carbon coatings for medical implants (2007) Journal of Achievements in Materials and Manufacturing Engineering, 20 (20), pp. 107-110;Jakubowski, W., Bartosz, G., Niedzielski, P., Szymanski, W., Walkowiak, B., Nanocrystalline diamond surface is resistant to bacterial colonization (2004) Diamond and Related Materials, 13 (10), pp. 1761-1763; Amaral, M., Abreu, C.S., Oliveira, F.J., Gomes, J.R., Silva, R.F., Biotribological performance of NCD coated Si3N4 -bioglass composites (2007) Diamond and Related Materials, 16, pp. 790-795; Amaral, M., Abreu, C.S., Oliveira, F.J., Gomes, J.R., Silva, R.F., Tribological characterization of NCD in physiological fluids (2008) Diamond and Related Materials, 17 (4-5), pp. 848-852; Nordsletten, L., Hgsen, A.K.M., Konttinen, Y.T., Santavirta, S., Aspenberg, P., Aasen, A.O., Human monocytes stimulation by particles of hydroxyapatite, silicon carbide and diamond: In vitro studies of new prosthesis coatings (1996) Biomaterials, 17 (15), pp. 1521-1527; Aspenberg, P., Anttila, A., Konttinen, Y.T., Benign response to particles of diamond and SiC: Bone chamber studies of new joint replacement coating materials in rabbits (1996) Biomaterials, 17 (8), pp. 807-812; Tang, L., Tsai, C., Gerberich, W.W., Kruckeberg, L., Kania, D.R., Biocompatibility of chemical-vapour-deposited diamond (1995) Biomaterials, 16 (6), pp. 483-488; Bakowicz-Mitura, K., Bartosz, G., Mitura, S., Influence of diamond powder particles on human gene expression (2007) Surface Coatings Technology, 201 (13), pp. 6131-6135; Kulisch, W., Popov, C., Bliznakov, S., Surface and bioproperties of nanocrystalline diamond/amorphous carbon nanocomposite films (2007) Thin Solid Films, 515 (23), pp. 8407-8411; Popov, C., Kulisch, W., Reithmaier, J.P., Bioproperties of nanocrystalline diamond/amorphous carbon composite films (2007) Diamond and Related Materials, 16, pp. 735-739; Rubio-Retama, J., Hernando, J., Lpez-Ruiz, B., Synthetic nanocrystalline diamond as a third-generation biosensor support (2006) Langmuir, 22 (13), pp. 5837-5842; Siew, P.S., Loh, K.P., Poh, W.C., Zhang, H., Biosensing properties of nanocrystalline diamond film grown on polycrystalline diamond electrodes (2005) Diamond and Related Materials, 14, pp. 426-431; Wenmackers, S., Christiaens, P., Daenen, M., DNA attachment to nanocrystalline diamond films (2005) Physica Status Solidi (A), 202 (11), pp. 2212-2216; Yang, W., Hamers, R.J., Fabrication and characterization of a biologically sensitive field-effect transistor using a nanocrystalline diamond thin film (2004) Applied Physics Letters, 85 (16), pp. 3626-3628; Steinmller-Nethl, D., Kloss, F.R., Najam-Ul-Haq, M., Strong binding of bioactive BMP-2 to nanocrystalline diamond by physisorption (2006) Biomaterials, 27 (26), pp. 4547-4556; Williams, D., Revisiting the definition of biocompatibility (2003) Medical Device Technology, 14 (8), pp. 10-13; Kue, R., Sohrabi, A., Nagle, D., Frondoza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like MG63 cells on silicon nitride ceramic discs (1999) Biomaterials, 20 (13), pp. 1195-1201; Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clinical Orthopaedics and Related Research, (244), pp. 296-301; Amaral, M., Costa, M.A., Lopes, M.A., Silva, R.F., Santos, J.D., Fernandes, M.H., Si 3 N 4 -bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and support the osteogenic differentiation of human bone marrow cells (2002) Biomaterials, 23 (24), pp. 4897-4906; Belmonte, M., Fernandes, A.J.S., Costa, F.M., Oliveira, F.J., Silva, R.F., Adhesion behaviour assessment on diamond coated silicon nitride by acoustic emission (2003) Diamond and Related Materials, 12, pp. 733-737; Amaral, M., Fernandes, A.J.S., Vila, M., Oliveira, F.J., Silva, R.F., Growth rate improvements in the hot-filament CVD deposition of nanocrystalline diamond (2006) Diamond and Related Materials, 15 (11-12), pp. 1822-1827; Almeida, F.A., Amaral, M., Oliveira, F.J., Fernandes, A.J.S., Silva, R.F., Nano to micrometric HFCVD diamond adhesion strength to Si3N4 (2007) Vacuum, 81 (11-12), pp. 1443-1447; Trigo Cabral, M.C., Costa, M.A., Fernandes, M.H., In vitro models of periodontal cells: A comparative study of long-term gingival, periodontal ligament and alveolar bone cell cultures in the presence of -glycerophosphate and dexamethasone (2007) Journal of Materials Science, 18 (6), pp. 1079-1088; Coelho, M.J., Trigo Cabral, A., Fernandes, M.H., Human bone cell cultures in biocompatibility testingpart I: Osteoblastic differentiation of serially passaged human bone marrow cells cultured in -MEM and in DMEM (2000) Biomaterials, 21 (11), pp. 1087-1094; Alberts, B., Johnson, A., Lewis, J., Ratt, M., Roberts, K., Walter, P., The cytoskeleton (2002) Molecular Biology of the Cell, , 4th New York, NY, USA Garland Science; Fawcett, D.W., Connective tissue (1994) A Textbook of Histology, pp. 133-169. , 12th New York, NY, USA Chapman Hall; Freshney, R.I., Biology of cultured cells (2000) Culture of Animal Cells: A Manual of Basic Technique, pp. 9-18. , 4th New York, NY, USA Wiley-Liss; Biological evaluation of medical devicespart 5: Tests for in vitro cytotoxicity, , International Organization for Standardization, Geneva, Switzerland, 1992; Okrj, W., Kamiska, M., Klimek, L., Szymaski, W., Walkowiak, B., Blood platelets in contact with nanocrystalline diamond surfaces (2006) Diamond and Related Materials, 15 (10), pp. 1535-1539; Popov, C., Kulisch, W., Jelinek, M., Bock, A., Strnad, J., Nanocrystalline diamond/amorphous carbon composite films for applications in tribology, optics and biomedicine (2006) Thin Solid Films, 494 (1-2), pp. 92-97; Kalbacova, M., Kalbac, M., Dunsch, L., The effect of SWCNT and nano-diamond films on human osteoblast cells (2007) Physica Status Solidi (B), 244 (11), pp. 4356-4359; Chong, K.F., Loh, K.P., Vedula, S.R.K., Cell adhesion properties on-photochemically functionalized diamond (2007) Langmuir, 23 (10), pp. 5615-5621; Bajaj, P., Akin, D., Gupta, A., Ultrananocrystalline diamond film as an optimal cell interface for biomedical applications (2007) Biomedical Microdevices, 9 (6), pp. 787-794; Stein, G.S., Lian, J.B., Molecular mechanisms mediating proliferation/differentiation interrelationships during progressive development of the osteoblast phenotype (1993) Endocrine Reviews, 14 (4), pp. 424-442; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testingpart II: Effect of ascorbic acid, -glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21 (11), pp. 1095-1102; Sikavitsas, V.I., Temenoff, J.S., Mikos, A.G., Biomaterials and bone mechanotransduction (2001) Biomaterials, 22 (19), pp. 2581-2593; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21 (17), pp. 1803-1810; Webster, T.J., Smith, T.A., Increased osteoblast function on PLGA composites containing nanophase titania (2005) Journal of Biomedical Materials Research Part A, 74 (4), pp. 677-686; Kay, S., Thapa, A., Haberstroh, K.M., Webster, T.J., Nanostructured polymer/nanophase ceramic composites enhance osteoblast and chondrocyte adhesion (2002) Tissue Engineering, 8 (5), pp. 753-761; Balasundaram, G., Sato, M., Webster, T.J., Using hydroxyapatite nanoparticles and decreased crystallinity to promote osteoblast adhesion similar to functionalizing with RGD (2006) Biomaterials, 27 (14), pp. 2798-2805; Kaplan, F.S., Hayes, W.C., Keaveny, T.M., Boskey, A., Einhorn, T.A., Iannotti, J.P., Simon, S.P., Form and function of bone (1994) Orthopedic Basic Science, pp. 127-185. , Columbus, Ohio, USA American Academy of Orthopedic Surgeons; Palin, E., Liu, H., Webster, T.J., Mimicking the nanofeatures of bone increases bone-forming cell adhesion and proliferation (2005) Nanotechnology, 16 (9), pp. 1828-1835; Siegel, R.W., Creating nanophase materials (1996) Scientific American Magazine, 275 (6), pp. 74-79; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Specific proteins mediate enhanced osteoblast adhesion on nanophase ceramics (2000) Journal of Biomedical Materials Research, 51 (3), pp. 475-483; Webster, T.J., Schadler, L.S., Siegel, R.W., Bizios, R., Mechanisms of enhanced osteoblast adhesion on nanophase alumina involve vitronectin (2001) Tissue Engineering, 7 (3), pp. 291-301

Nanocrystalline diamond: In vitro biocompatibility assessment by MG63 and human bone marrow cells cultures - Amaral, M.; Dias, A.G.; Gomes, P.S.; Lopes, M.A.; Silva, R.F.; Santos, J.D.; Fernandes, M.H. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2008)
Nanocrystalline diamond (NCD) has a great potential for prosthetic implants coating. Nevertheless, its biocompatibility still has to be better understood. To do so, we employed several materials characterization techniques (SEM, AFM, micro-Raman spectroscopy) and cell culture assays using MG63 osteoblast-like and human bone marrow cells. Biochemical routines (MTT assays, Lowry's method, ALP activity) supported by SEM and confocal microscopy characterization were carried out. We used silicon nitride (Si 3N 4) substrates for NCD coatings based on a previous demonstration of the superior adhesion and tribological performance of these NCD coated ceramics. Results demonstrate an improved human osteoblast proliferation and the stimulation of differentiated markers, like ALP activity and matrix mineralization, compared with standard polystyrene tissue culture plates. The nanometric featuring of NCD, associated to its chemical affinity are key points for bone regeneration purposes. © 2007 Wiley Periodicals, Inc.
Cited By (since 1996): 25Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31742PubMed ID: 18085649Language of Original Document: EnglishCorrespondence Address: Silva, R. F.; CICECO, Department of Ceramics and Glass Engineering, University of Aveiro, 3810-193 Aveiro, Portugal; email: rsilva@cv.ua.ptChemicals/CAS: diamond, 7782-40-3; polystyrene, 9003-53-6; silicon nitride, 12033-89-5; Alkaline Phosphatase, EC 3.1.3.1; Ceramics; Coated Materials, Biocompatible; Diamond, 7782-40-3; Silicon Compounds; silicon nitride, 12033-89-5References: Ratner, B.D., Hoffman, A.S., Schoen, A.S., Lemons, J.E., (1996) Biomaterials Science: An Introduction to Materials in Medicine, , New York: Academic Press;;Emery, D.F.G., Clarke, H.J., Grover, M.L., Stanmore total hip replacement in younger patients: Review of a group of patients under 50 years of age at operation (1997) J Bone Joint Surg, 79, pp. 240-246; Shane, A.C., Monique, C., Yogesh, K.V., Erick, M.S., Michelle, D.M., David Moore, K., Surface crystalline phases and nanoindentation hardness of explanted zirconia femoral heads (2003) J Mater Sci: Mater Med, 14, pp. 863-867; Shane, A.C., Marc, D.F., Yogesh, K.V., William, R.L., Jack, E.L., Shanna, W., Ramakrishna, V., Nanostructured ceramics for biomedical implants (2002) J Nanosci Nanotechnol, 2, pp. 293-312; Palin, E., Liu, H., Webster, T.J., Mimicking the nanofeatures of bone increases bone-forming cell adhesion and proliferation (2005) Nanotechnology, 16, pp. 1828-1835; Webster, T.J., Siegel, R.W., Bizios, R., Osteoblast adhesion on nanophase ceramics (1999) Biomaterials, 20, pp. 1221-1227; Price, R.L., Haberstroh, K.M., Webster, T.J., Enhanced functions of osteoblasts on nanostructured surfaces of carbon and alumina (2003) Med Biol Eng Comput, 41, pp. 372-375; Perla, V., Webster, T.J., Better osteoblast adhesion on nanoparticulate selenium - A promising orthopedic implant material (2005) J Biomed Mater Res, 75 A, pp. 356-364; Fries, M.D., Vohra, Y.K., Nanostructure diamond film deposition on curved surfaces of metallic temporomandibular joint implant (2002) J Phys D: Appl Phys, 35, pp. L105-L107; Papo, M.J., Catledge, S.A., Vohra, Y.K., Mechanical wear behaviour of nanocrystalline and multilayer diamond coatings on temporomandibular joint implants (2004) J Mater Sci: Mater Med, 15, pp. 773-777; Aspenberg, P., Antilla, A., Konttinen, Y.T., Lappalainen, R., Goodman, S.B., Nordsletten, L., Santavirta, S., Benign response to particles of diamond and SiC: Bone chamber studies of new joint replacement coating materials in rabbits (1996) Biomaterials, 17, pp. 807-812; Nordsletten, L., Hogasen, A.K.M., Konttinen, Y.T., Santavirta, S., Aspenberg, P., Aasen, A.O., Human monocytes stimulation by particles of hydroxyapatite, silicon carbide and diamond: In vitro studies of new prosthesis coatings (1996) Biomaterials, 17, pp. 1521-1527; Mitura, S., Mitura, A., Niedzielski, P., Couvrat, P., Nanocrystalline diamond coatings (1999) Chaos Solitons Fractals, 10, pp. 2165-2176; Mitura, K., Niedzielski, P., Grzegorz, B., Moll, J., Walkowiak, B., Pawlowska, Z., Louda, P., Mitura, S., Interactions between carbon coatings and tissue (2006) Surf Coat Technol, 201, pp. 2117-2123; Garguilo, J.M., Davis, B.A., Buddie, M., Köck, F.A.M., Nemanich, R.J., Fibrinogen adsorption onto microwave plasma chemical vapour deposited diamond films (2004) Diamond Relat Mater, 13, pp. 595-599; Tang, L., Tsai, C., Gerberich, W.W., Kruckeberg, L., Kania, D.R., Biocompatibility of chemical-vapour deposited diamond (1995) Biomaterials, 16, pp. 483-488; Narayan, R.J., Wei, W., Jin, C., Andara, M., Agarwal, A., Gerhardt, R.A., Shih, C., Singh, R.N., Microstructural and biological properties of nanocrystalline diamond coatings (2006) Diamond Relat Mater, 15, pp. 1935-1940; Popov, C., Kulisch, W., Jelinek, M., Bock, A., Strnad, J., Nanocrystalline diamond/amorphous carbon composite films for applications in tribology, optics and biomedicine (2006) Thin Solid Films, 494, pp. 92-97; Nethl, D.S., Kloss, F.R., Haq, M.N.U., Rainer, M., Larsson, K., Linsmeier, C., Köhler, G., Bonn, G., Strong binding of bioactive BMP-2 to nanocrystalline diamond by physisorption (2006) Biomaterials, 27, pp. 4547-4556; Silva, V.A., Costa, F.M., Fernandes, A.J.S., Nazaré, M.H., Silva, R.F., Influence of SiC particle addition on the nucleation density and adhesion strength of MPCVD diamond coatings on S13N4 substrates (2000) Diamond Relat Mater, 9, pp. 483-488; Kue, R., Sahrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201; Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clin Orthop, 244, pp. 296-301; Amaral, M., Costa, M.A., Lopes, M.A., Silva, R.F., Santos, J.D., Fernandes, M.H., Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and support the osteogenic differentiation of human bone marrow cells (2002) Biomaterials, 23, pp. 4897-4906; Belmonte, M., Fernandes, A.J.S., Costa, F.M., Oliveira, F.J., Silva, R.F., Adhesion behaviour assessment on diamond coated silicon nitride by acoustic emission (2003) Diamond Relat Mater, 12, pp. 733-737; Coelho, M.J., Trigo Cabrai, A., Fernandes, M.H., Human bone cell cultures in biocompatibility testing, Part 1: Osteoblastic differentiation of serially passaged human bone marrow cells cultured in α-MEM and in DMEM (2000) Biomaterials, 21, pp. 1087-1094; Clifford, C.J., Downes, S., A comparative study of the use of colorimetric assays in the assessment of biocompatibility (1996) J Mater Sci: Mater Med, 7, pp. 637-643; Ciapetti, G., Cenni, E., Pratelli, L., Pizzoferrato, A., In vitro evaluation of cell/biomaterial interaction by MTT assay (1993) Biomaterials, 14, pp. 359-364; Ferrari AC, Robertson J. Origin of the 1150 cm -1 Raman mode in nanocrystalline diamond. Phys Rev B 2001;63:121405-1-4Pfeiffer, R., Kuzmany, H., Knoll, P., Bokova, S., Salk, N., Günther, B., Evidence for trans-polyacetylene in nano-crystalline diamond films (2003) Diamond Relat Mater, 12, pp. 268-271; Fernandes, A.J.S., Neto, M.A., Almeida, F.A., Silva, R.F., Costa, F.M., Nano- and micro-crystalline diamond growth by MPCVD in extremely poor hydrogen uniform plasmas (2007) Diamond Relat Mater, 16, pp. 757-761; Almeida, F.A., Amaral, M., Oliveira, F.J., Fernandes, A.J.S., Silva, R.F., Nano to micrometric HFCVD diamond adhesion strength to Si 3N 4 (2007) Vacuum, 81, pp. 1443-1447; Abreu, C.S., Amaral, M., Oliveira, F.J., Fernandes, A.J.S., Gomes, J.R., Silva, R.F., Enhanced performance of HFCVD nanocrystalline diamond self-mated tribosystems by plasma pretreatments on silicon nitride substrates (2006) Diamond Relat Mater, 15, pp. 2024-2028; Abreu, C.S., Amaral, M., Fernandes, A.J.S., Oliveira, F.J., Silva, R.F., Gomes, J.R., Friction and wear performance of HFCVD nano-crystalline diamond coated silicon nitride ceramics (2006) Diamond Relat Mater, 15, pp. 739-744; Stein, G.S., Lian, J.B., Molecular mechanisms mediated proliferation- differentiation interrelationships during progressive development of the osteoblast phenotype (1993) Endocr Rev, 14, pp. 424-442; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing, Part 2: Effect of ascorbic acid, β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Kaplan, F.S., Hayes, W.C., Keaveny, T.M., Boskey, A., Einhorn, T.A., Iannotti, J.P., Form and function of bone (1994) Orthopedic Basic Science, pp. 127-185. , Simon SP, editor, Columbus, OH: American Academy of Orthopedic Surgeons;; Webster, T.J., Ejiofor, J.U., Increased osteoblast adhesion on nanophase metals: Ti, Ti6A14V, and CoCrMo (2004) Biomaterials, 25, pp. 4731-4739; Kay, S., Thapa, A., Haberstroh, K.M., Webster, T.J., Nanostructured polymer/nanophase ceramic composites enhance osteoblast and chondrocyte adhesion (2002) Tissue Eng, 8, pp. 753-761; Webster, T.J., Smith, T.A., Increased osteoblast function on PLGA composites containing nanophase titania (2005) J Biomed Mater Res A, 74, pp. 677-686; Balasundaram, G., Sato, M., Webster, T.J., Using hydroxyapatite nanoparticles and decreased crystallinity to promote osteoblast adhesion similar to functionaizing with RGD (2006) Biomaterials, 27, pp. 2798-2805; Webster, T.J., (2004) Proteins: Structure and interactions patterns to solid surfaces, pp. 1-16. , editors. Encyclopedia of Nanoscience and Nanotechnology. New York: Marcel Dekker; Siegel RW. Creating nanophase materials. Sci Am (Int Ed) 1996;275:74-79Webster, T.J., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21, pp. 1803-1810; Webster, T.J., Enhanced osteoclast-like cell functions on nano-phase ceramics (2001) Biomaterials, 22, pp. 1327-1333; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Specific proteins mediate enhanced osteoblast adhesion on nano-phase ceramics (2000) J Biomed Mater Res, pp. 51475-51483; Webster, T.J., Schadler, L.S., Siegel, R.W., Bizios, R., Mechanisms of enhanced osteoblast sdhesion on nanophase alumina involve vitronectin (2001) Tissue Eng, 7, pp. 291-301
Keywords: adult; alkaline phosphatase; ALP activity; Animal cell culture; Architectural acoustics; article; Atomic force microscopy; Biocompatibility; Bone; bone marrow cell; Bone Marrow Cells; Bone Regeneration; Cell culture; cell proliferation; cell survival; Cells; Cells, Cultured; ceramics; Cladding (coating); Coated Materials, Biocompatible; confocal microscopy; controlled study; diamond; Diamonds; enzyme activity; extracellular matrix; human; Human bone marrow cells; human cell; Humans; Imaging techniques; Implants (surgical); In vitro biocompatibility; in vitro selection; Joint replacement; male; Materials characterization; materials testing; Micro-Raman spectroscopy; Microscopic examination; Microscopy, Atomic Force; Microscopy, Confocal; Microscopy, Electron, Scanning; mineralization; MTT assaying; Nano-crystalline diamond; nanocrystal; Nanocrystalline alloys; Nanocrystalline materials; nanoparticles; Nanostructured materials; Nitrides; Nonmetals; osteoblast; Osteoblasts; polystyrene; Prostheses and Implants; Raman spectrometry; Scanning electron microscopy; Secondary emission; Silicon; Silicon compounds; Silicon nitride; Spectrum Analysis, Raman; Surface Properties; Tissue engineering

Omniview-SisPorto® 3.5 - A central fetal monitoring station with online alerts based on computerized cardiotocogram+ST event analysis - Ayres-de-Campos, D.; Sousa, P.; Costa, A.; Bernardes, J. (Journal of Perinatal MedicineJ. Perinat. Med., 2008)
Visual analysis of cardiotocograms is poorly reproducible and is currently recognized as the main weakness of the STAN® methodology. The Omniview-SisPorto® 3.5 program is the most recent version of a central monitoring system that provides visual and sound alerts, based on computer analysis of cardiotocographic and ST event features. This paper describes the program's main characteristics and provides an overview of the system's online alerts. Omniview-SisPorto® 3.5 is the first central monitoring system to incorporate computerized analysis of cardiotocographic and ST event features, providing health professionals with online alerts for minor and major changes in monitored signals. The system is currently undergoing extensive clinical evaluation. © 2008 by Walter de Gruyter.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JPEMAdoi: 10.1515/JPM.2008.030Language of Original Document: EnglishCorrespondence Address: Ayres-De-Campos, D.; Departmento Ginecologia e Obstetricia, Faculdade de Medicina, Universidade Do Porto, Alameda Hernani Monteiro, 4200-319 Porto, Portugal; email: sisporto@med.up.ptTradenames: Omniview-SisPorto 3.5 system, SpeculumManufacturers: SpeculumReferences: Amer-Wahlin, I., Arulkumaran, S., Hagberg, H., Marsal, K., Visser, G., Fetal electrocardiogram: ST waveform analysis in intrapartum surveillance (2007) Br J Obstet Gynaecol, 114, pp. 1191-1193;Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marquesde-Sá, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Ayres-de-Campos, D., Bernardes, J., Comparison of fetal heart rate baseline estimation by SisPorto 2.01 and a consensus of clinicians (2004) Eur J Obstet Gynecol Reprod Biol, 117, pp. 174-178; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., SisPorto Multicentre Validation Study Group. Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118, pp. 52-60; Ayres-de-Campos, D., Bernardes, J., Kwee, A., Westehuis, M., Visser, G.H.A., Computer quantification of short-term variability as an adjunct to fetal electrocardiographic monitoring (2007) Br J Obstet Gynaecol, 114, pp. 1446-1447; Bernardes, J., Moura, C., Marques de, S.J., Pereira Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Electronic fetal heart rate monitoring: Research guidelines for interpretation (1997) Am J Obstet Gynecol, 177, pp. 1385-1390. , National Institute of Child Health and Human Development Research Planning Workshop; Neilson, J.P., Fetal electrocardiogram (ECG) for fetal monitoring during labor (2006) Cochrane Database of Systematic Reviews, (3); Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-165; (2001) Evidence-based clinical guideline: The use of electronic fetal monitoring, , RCOG, Royal College of Obstetricians and Gynaecologists, London, RCOG Press; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring (1987) Int J Gynecol Obstet, 25, pp. 159-167
Keywords: article; Cardiotocography; computer program; Computer-assisted; Electrocardiography; Female; Fetal; Fetal hypoxia; Fetal monitoring; fetus hypoxia; fetus monitoring; Heart rate; human; Humans; instrumentation; online system; Pregnancy; priority journal; Signal processing; ST segment

Osteoblast adhesion and morphology on TiO 2 depends on the competitive preadsorption of albumin and fibronectin - Sousa, S.R.; Lamghari, M.; Sampaio, P.; Moradas-Ferreira, P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2008)
This study aims at assessing the influence of the competitive preadsorption of human serum albumin (HSA) and human plasma fibronectin (FN) from binary solutions and 10% plasma on MC3T3-E1 osteoblast adhesion and morphology on two types of TiO 2 substrates. One was commercially pure titanium with a titanium oxide layer formed in an H 2O 2 solution and the other TiO 2 sputtered on Si (Sousa et al., Langmuir 2004; 20:9745-9754.). The strategy applied in the present investigation was to compare osteoblast adhesion to surfaces preadsorbed with HSA, FN, HSA/FN = 1, HSA/FN = 200, and 10% plasma. The adsorption of proteins was evaluated measuring the amount and the effectiveness of binding with radiolabeled proteins, 125I-FN and 125I-HSA. Our results indicated that MC3T3-E1 osteoblast adhesion correlates well with the amounts of FN and HSA adsorbed on TiO 2 surfaces. Also, we found that fewer osteoblasts adhered to both substrates preadsorbed with HSA, HSA/FN = 200, and 10% plasma, after 4 and 24 h, than to the surfaces preadsorbed with FN and HSA/FN = 1. For the latter, FN was able to compensate the inhibitory effect of HSA on osteoblast adhesion. Therefore, the presence of lower amounts of coadsorbed albumin may improve presentation of FN in a more integrin-recognized conformation, suggesting that some degree of molecular packing prevents loss of integrin-binding activity. FN reversibility does not seem to be dependent on the HSA/FN adsorption mass ratio in solution, suggesting that FN competitively adsorbs to TiO 2 in a favorable conformation and does not suffers subsequent conformational changes allowing exchange with other FN molecules in solution. © 2007 Wiley Periodicals, Inc.
Cited By (since 1996): 34Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31201PubMed ID: 17607748Language of Original Document: EnglishCorrespondence Address: Sousa, S.R.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomaterials, R. do Campo Alegre, 823, 4150-180 Porto, Portugal; email: ssousa@ibmc.up.ptChemicals/CAS: fibronectin, 86088-83-7; human serum albumin, 9048-49-1; hydrogen peroxide, 7722-84-1; iodine 125, 14158-31-7, 22822-81-7; titanium dioxide, 1317-70-0, 1317-80-2, 13463-67-7, 51745-87-0; Albumins; Coloring Agents; Fibronectins; Iodine Radioisotopes; Neutral Red, 553-24-2; titanium dioxide, 13463-67-7; Titanium, 7440-32-6References: Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681;Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalized, self-assembled monolayers of alkane-thiolates on gold (1997) Langmuir, 13, pp. 3404-3413; Malmsten, M., Lassen, B., Competitive adsorption at hydrophobic surfaces from binary protein systems (1994) J Colloid Interface Sci, 166, pp. 490-498; Koenig, A.L., Gambillara, V., Grainger, D.W., Correlating fibronectin adsorption with endothelial cell adhesion and signaling on polymer substrates (2003) J Biomed Mater Res A, 64, pp. 20-37; Horbett, T.A., The role of adsorbed proteins in animal cell adhesion (1994) Colloids Surf B, 2, pp. 225-240; Huang, H.H., Ho, C.T., Lee, T.H., Lee, T.L., Liao, K.K., Chen, F.L., Effect of surface roughness of ground titanium on initial cell adhesion (2004) Biomol Eng, 21, pp. 93-97; Vitte, J., Benoliel, A.M., Pierres, A., Bongrand, P., Is there a predictable relationship between surface physical-chemical properties and cell behaviour at the interface? (2004) Eur Cell Mater, 7, pp. 52-63; Tsai, W.B., Grunkemeier, J.M., McFarland, C.D., Horbett, T.A., Platelet adhesion to polystyrene-based surfaces preadsorbed with plasmas selectively depleted in fibrinogen, fibronectin, vitronectin, or von Willebrand's factor (2002) J Biomed Mater Res, 60, pp. 348-359; Grainger, D.W., Pavon-Djavid, G., Migonney, V., Josefowicz, M., Assessment of fibronectin conformation adsorbed to polytetrafluoroethylene surfaces from serum protein mixtures and correlation to support of cell attachment in culture (2003) J Biomater Sci Polym Ed, 14, pp. 973-988; Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Protein adsorption on 18-alkyl chains immobilized on hydroxyl-terminated self-assembled monolayers (2005) Biomaterials, 26, pp. 3891-3899; Culp, L.A., Sukenik, C.N., Cell type-specific modulation of fibronectin adhesion functions on chemically-derivatized self-assembled monolayers (1998) J Biomater Sci Polym Ed, 9, pp. 1161-1176; Baugh, L., Vogel, V., Structural changes of fibronectin adsorbed to model surfaces probed by fluorescence resonance energy transfer (2004) J Biomed Mater Res A, 69, pp. 525-534; McClary, K.B., Ugarova, T., Grainger, D.W., Modulating fibroblast adhesion, spreading, and proliferation using self-assembled monolayer films of alkylthiolates on gold (2000) J Biomed Mater Res, 50, pp. 428-439; Sousa, S.R., Moradas-Ferreira, P., Melo, L.V., Saramago, B., Barbosa, M.A., Human serum albumin adsorption on TiO 2 from single protein solutions and from plasma (2004) Langmuir, 20, pp. 9745-9754; Gehanno, V., Freitas, P.P., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Soares, J.C., Silva, M.F., Ion beam deposition of Mn-Ir spin valves (1999) IEEE Trans Magn, 35, pp. 4361-4367; Iodine-125. A Guide to Radioiodination Techniques. Little Chalfont, UK: Amersham Life Science; 1993. p 64Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., Interactions between calcium, phosphate, and albumin on the surface of titanium (2001) J Biomed Mater Res, 55, pp. 45-53; Sousa, S.R., Moradas-Ferreira, P., Barbosa, M., TiO 2 type influences fibronectin adsorption (2005) J Mater Sci Mater Med, 16, pp. 1173-1178; McFarland, C.D., Mayer, S., Scotchford, C., Dalton, B.A., Steele, J.G., Downes, S., Attachment of cultured human bone cells to novel polymers (1999) J Biomed Mater Res, 44, pp. 1-11; McFarland, C.D., Thomas, C.H., DeFilippis, C., Steele, J.G., Healy, K.E., Protein adsorption and cell attachment to patterned surfaces (2000) J Biomed Mater Res, 49, pp. 200-210; Yang, Y.Z., Cavin, R., Ong, J.L., Protein adsorption on titanium surfaces and their effect on osteoblast attachment (2003) J Biomed Mater Res A, 67, pp. 344-349; MacDonald, D.E., Rapuano, B.E., Deo, N., Stranick, M., Somasundaran, P., Boskey, A.L., Thermal and chemical modification of titanium-aluminum-vanadium implant materials: Effects on surface properties, glycoprotein adsorption, and MG63 cell attachment (2004) Biomaterials, 25, pp. 3135-3146; Steele, J.G., Johnson, G., McFarland, C., Dalton, B.A., Gengenbach, T.R., Chatelier, R.C., Underwood, P.A., Griesser, H.J., Roles of serum vitronectin and fibronectin in initial attachment of human vein endothelial-cells and dermal fibroblasts on oxygen-containing and nitrogen-containing surfaces made by radiofrequency plasmas (1994) J Biomater Sci Polym Ed, 6, pp. 511-532; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) J Biomed Mater Res A, 66, pp. 247-259; Jenney, C.R., Anderson, J.M., Adsorbed serum proteins responsible for surface dependent human macrophage behavior (1999) J Biomed Mater Res, 49, pp. 435-447; Webb, K., Hlady, V., Tresco, P.A., Relationships among cell attachment, spreading, cytoskeletal organization, and migration rate for anchorage-dependent cells on model surfaces (2000) J Biomed Mater Res, 49, pp. 362-368; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., Rat bone marrow stromal cell osteogenic differentiation and fibronectin adsorption on chitosan membranes: The effect of the degree of acetylation (2005) J Biomed Mater Res A, 75, pp. 387-397; Scotchford, C.A., Gilmore, C.P., Cooper, E., Leggett, G.J., Downes, S., Protein adsorption and human osteoblast-like cell attachment and growth on alkylthiol on gold self-assembled monolayers (2002) J Biomed Mater Res, 59, pp. 84-99; Pettit, D.K., Horbett, T.A., Hoffman, A.S., Influence of the substrate binding characteristics of fibronectin on corneal epithelial cell outgrowth (1992) J Biomed Mater Res, 26, pp. 1259-1275; Steele, J.G., Johnson, G., Underwood, P.A., Role of serum vitronectin and fibronectin in adhesion of fibroblasts following seeding onto tissue-culture polystyrene (1992) J Biomed Mater Res, 26, pp. 861-884
Keywords: 2; 3T3 Cells; Adsorption; Albumins; animal cell; Animals; article; binding kinetics; cell adhesion; Coloring Agents; Competitive protein adsorption; controlled study; cytoskeleton; Data Interpretation, Statistical; Fibronectin; Fibronectins; FN; HSA; human serum albumin; hydrogen peroxide; iodine 125; Iodine Radioisotopes; isotope labeling; Mice; Microscopy, Confocal; mouse; neutral red; nonhuman; osteoblast; Osteoblast adhesion; Osteoblasts; Protein radiolabeling; Proteins; Radiology; Solutions; Sterilization; surface property; TiO; Titanium; Titanium dioxide

PLD bioactive ceramic films: The influence of CaO-P 2O 5 glass additions to hydroxyapatite on the proliferation and morphology of osteblastic like-cells - Oliveira, G.M.; Ferraz, M.P.; González, P.G.; Serra, J.; Leon, B.; Pèrez-Amor, M.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2008)
This work consists on the evaluation of the in vitro performance of Ti6Al4V samples PLD (pulsed laser deposition) coated with hydroxyapatite, both pure and mixed with a CaO-P 2O 5 glass. Previous studies on immersion of PLD coatings in SBF, showed that the immersion apatite films did not present the usual cauliflower morphology but replicated the original columnar structure and exhibited good bioactivity. However, the influence of glass associated to hydroxyapatite concerning adhesion, proliferation and morphology of MG63 cells on the films surface was unclear. In this study, the performance of these PLD coated samples was evaluated, not only following the physical-chemical transformations resulting from the SBF immersion, but also evaluating the cytocompatibility in contact with osteoblast-like MG63 cells. SEM and AFM confirmed that the bioactive ceramic PLD films reproduce the substrate's surface topography and that the films presented good adherence and uniform surface roughness. Physical-chemical phenomena occurring during immersion in SBF did not modify the original columnar structure. In contact with MG63 cells, coated samples exhibited very good acceptance and cytocompatibility when compared to control. The glass mixed with hydroxyapatite induced higher cellular proliferation. Cells grown on these samples presented many filipodia and granular structures, typical features of osteoblasts. © 2007 Springer Science+Business Media, LLC.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-007-3331-zPubMed ID: 18058197Language of Original Document: EnglishCorrespondence Address: Oliveira, G. M.; Universidade Fernando Pessoa, Praça Nove de Abril 349, 4249-004 Porto, Portugal; email: gisela@ufp.ptChemicals/CAS: calcium oxide, 1305-78-8; hydroxyapatite, 1306-06-5, 51198-94-8; oxide, 16833-27-5; Biocompatible Materials; Calcium Compounds; Ceramics; Durapatite, 1306-06-5; Oxides; Phosphorus Compounds; Polystyrenes; lime, 1305-78-8; phosphorus pentoxide, 1314-56-3References: Hench, L.L., (1991) J. Am. Ceram. Soc., 74, p. 1487;Hench, L.L., (1998) Biomaterials, 19, p. 1419; Park, S.H., Llinás, A., Goel, V.K., Keller, J.C., (2000) The Biomedical Engineering Handbook, , Edited by: J. D. BRONZINO (CRC Press, LLC, Boca Raton); Hench, L.L., (1994) 7th International Symposium on Ceramics in Medicine, p. 3. , Edited by: Ö. H. A. A. Y. URPO (Butterworth-Heinemann Ltd Oxford, England); Kokubo, T., (1991) Biomaterials, 12, p. 155; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, p. 6. , JAAS Takayan Press. Ishiyaku euroAmerica, Inc Tokyo; Orlovskii, V.P., Komlev, V.S., Barinov, S.M., (2002) Inorg. Mater., 38, p. 973; Kenny, S.M., Buggy, M., (2003) J. Mater. Sci. Mat. Med., 14, p. 923; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., (1995) J. Mat. Sci. Mat. Med., 6, p. 348; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., (2001) J. Mater. Sci.: Mater. Med., 12, p. 629; Ferraz, M.P., Monteiro, F.J., Gião, D., Léon, B., Gonzalez, P., Liste, S., Serra, J., Perez-Amor, M., (2004) Key Eng. Mat., 254-256, p. 347; Porter, A.E., Hobbs, L.W., Benezra Rosen, V., Spector, M., (2002) Biomaterials, 23, p. 725; Kim, H.-K., Jang, J.-W., Lee, C.-H., (2004) J. Mater. Sci.: Mater. Med., 15, p. 825; Harada, Y., Wang, J.-T., Doppalapudi, V.A., Willis, A.A., Jasty, M., Harris, W.H., Nagase, M., Goldring, S.R., (1996) J. Biomed. Mater. Res., 31, p. 19; Arias, J.L., Mayor, M.B., Pou, J., Léon, B., Pérez-Amor, M., (2000) Appl. Surf. Sci., 154-155, p. 434; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., (1996) J. Mater. Sci.: Mater. Med., 7, p. 187; Arias, J.L., Mayor, M.B., Pou, J., Leng, Y., Léon, B., Pérez-Amor, M., (2003) Biomaterials, 24, p. 3403; Arias, J.L., Mayor, M.B., Pou, J., Léon, B., Pérez-Amor, M., (2002) Appl. Surf. Sci., 182, p. 448; Arias, J.L., Mayor, M.B., Pou, J., Léon, B., Pérez-Amor, M., (2002) Vaccum, 67, p. 653; Arias, J.L., Garcia-Sanz, F.J., Mayor, M.B., Chiussi, S., Pou, J., Léon, B., Pérez-Amor, M., (1998) Biomaterials, 19, p. 883; Mayor, M.B., Arias, J.L., Chiussi, S., Garcia, F., Pou, J., Léon, B., Pérez-Amor, M., (1998) Thin Solid Films, 317, p. 363; Kokubo, T., Kushitani, H., Sakka, S., Kitsuki, T., Yamamuro, T., (1990) J. Biomed. Mater. Res., 24, p. 721; Monteiro, F.J., Ferraz, M.P., Gião, D., Leon, B., Gonzalez, P., Liste, S., Serra, J., Perez-Amor, M., (2002) 17th European Conference on Biomaterials, pp. P65. , Edited by: E. S. F. Biomaterials (Barcelona, Spain); Lossdörfer, S., Schwartz, Z., Wang, L., Lohmann, C.H., Turner, J.D., Wieland, M., Cochran, D.L., Boyan, B.D., (2004) J. Biomed. Mater. Res, 70, p. 361; Bannister, S.R., Lohmann, C.H., Liu, Y., Sylvia, V.L., Cochran, D.L., Dean, D.D., Boyan, B.D., Schwartz, Z., (2002) J. Biomed. Mater. Res., 60, p. 164; Cleries, L., Fernandez-Pradas, J.M., Sardin, G., Morenza, J.L., (1998) Biomaterials, 19, p. 1483; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., (1996) J. Mater. Sci.: Mater. Med., 7, p. 21; Knabe, C., Klar, F., Fitzner, R., Radlanski, R.J., Gross, U., (2002) Biomaterials, 23, p. 3235; Garcia, F., Arias, J.L., Mayor, M.B., Pou, J., Rehman, I., Knowles, J., Best, S., Bonefield, W., (1998) J. Biomed. Mater. Res. (Appl. Biomater), 43, p. 69; Peng, P., Kumar, S., Voelcker, N.H., Szili, E., Smart, R.S.C., Griesser, H.J., (2006) J. Biomed. Mater. Res., 76, p. 347; Borsari, V., Giavaresi, G., Fini, M., Torriceli, P., Salito, A., Chiesa, R., Chiusoli, L., Giardino, R., (2005) J. Biomed. Mater. Res. Part B: Appl. Biomater., 75, p. 359; Massaro, C., Baker, M.A., Cosentino, F., Ramires, P.A., Klose, S., Milella, E., (2001) J. Biomed. Mater. Res., 58, p. 651; Bigi, A., Bracci, B., Cuisinier, F., Elkaim, R., Fini, M., Mayer, I., Mihailescu, I.N., Torricelli, P., (2005) Biomaterials, 26, p. 2381; Zeng, H., Lacefield, W.R., (2000) J. Biomed. Mater. Res., 50, p. 239; Clèries, L., Fernandez-Pradas, J.M., Morenza, J.L., (2000) Biomaterials, 21, p. 1861; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 45, p. 376; Li, P., Ducheyne, P., (1998) J. Biomed. Mater. Res., 41, p. 341; Weng, J., Liu, Q., Wolke, J.G., Zhang, X., De Groot, K., (1997) Biomaterials, 18, p. 1027; Tas, A.C., (2000) Biomaterials, 21, p. 1429; Kokubo, T., Kim, H.-M., Kawashita, M., (2003) Biomaterials, 24, p. 2161; Dewez, J.-L., Doren, A., Schneider, Y.-J., Rouxhet, P.G., (1999) Biomaterials, 20, p. 547; Anselme, K., Linez, P., Bigerelle, M., Le Maguer, D., Le Maguer, A., Hardouin, P., Hildebrand, H.F., Leroy, J.M., (2000) Biomaterials, 21, p. 1567; Okumura, A., Goto, M., Goto, T., Yoshinari, M., Masuko, S., Katsuki, T., Tanaka, T., (2001) Biomaterials, 22, p. 2263; Kim, H.J., Kim, S.H., Kim, M.S., Lee, E.J., Oh, H.G., Oh, W.M., Park, S.W., Dean, D.D., (2005) J. Biomed. Mater. Res., 74, p. 366
Keywords: Apatite; Apatite films; Bioactive ceramic films; Bioactive glass; Bioactivity; Bioceramics; Biocompatible Materials; Biofilms; Brassica oleracea var. botrytis; Calcium Compounds; calcium oxide; Cauliflower morphology; cell adhesion; cell proliferation; cell structure; cell survival; ceramics; Columnar structure; conference paper; controlled study; Durapatite; glass; human; human cell; Humans; hydroxyapatite; Lasers; materials testing; Microscopy, Atomic Force; Microscopy, Electron, Scanning; morphology; osteoblast; Osteoblasts; oxide; Oxides; phosphorous pentoxide; Phosphorus Compounds; Polystyrenes; priority journal; Pulsed laser deposition; unclassified drug

Structural studies of Na 2O-TiO 2-CaO-P 2O 5 system glasses investigated by FTIR and FT-Raman - Li, Y.; Weng, W.; Santos, J.D.; Lopes, A.M. (Physics and Chemistry of Glasses: European Journal of Glass Science and Technology Part BPhys. Chem. Glasses Euro. J. Glass Sci. Technol. Part B, 2008)
CaO-P 2O 5 based glasses are widely used as biomaterials due to their various chemical compositions, excellent bioactivity, adjustable biodegradation and suitable mechanical properties. The structures of Na 2O-TiO 2-CaO-P 2O 5 system glasses were investigated by FTIR and FT-Raman spectroscopies. The calcium phosphate glasses have chain-like structures based on Ti-O-P linkages containing [P 2O 7] 4- groups and [PO 4] 3- groups. Some amount of TiO 2 enters into the glass network, in which [TiO 4] tetrahedra connect with [PO 4] tetrahedra through the P-O-Ti bonds, the remaining TiO 2 exists into interspaces of [PO 4] tetrahedra. CaO connects the two linkages in the form of Ca-O-P bonds.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Li, Y.; College of Materials Science and Engineering, Nanjing University of Technology, Nanjing, 210009, China; email: lyanbao@163.comReferences: Hench, L.L., Glasses to turn on genes (2004) Glass Sci. Technol, 77, pp. 95-103;Hench, L.L., Third-generation gene-activating biomaterials (2003) Thermec'2003, Pts 1-5, pp. 179-184; Knowles, J.C., Phosphate based glasses for biomedical applications (2003) J. Mater. Chem, 13 (10), pp. 2395-2401; Hench, L.L., Xynos, I.D., Polak, J.M., Bioactive glasses for in situ tissue regeneration (2004) J. Biomater. Sci.-Polym. Ed, 15 (4), pp. 543-562; Kasuga, T., Bioactive calcium pyrophosphate glasses and glass-ceramics (2005) Acta Biomater, 1 (1), pp. 55-64; Rawson, H., Inorganic Glass-Forming System, Academic Press, London, YEAR, p. 155; Selvaraj, U., Rao, K.J., (1988) J. Non-Cryst. Solids, 104, p. 300; Chakraborty, S., Paul, A., (1989) J. Mater. Sci. Lett, 8, p. 1358; Shih, P.Y., Yung, S.W., Chin, T.S., (1999) J. Non-Cryst. Solids, 244, p. 211; Brow, R.K., (1997) Phys. Chem. Glasses, 38, p. 300; Kasuga, T., Abe, Y., Calcium phosphate invert glasses with soda and titania (1999) J. Non-Cryst. Solids, 243 (1), pp. 70-74; Kasuga, T., Abe, Y., Novel calcium phosphate ceramics prepared by powder sintering and crystallization of glasses in the pyrophosphate region (1998) J. Mater. Res, 13 (12), pp. 3357-3360; Zhang, Y., Santos, J.D., Microstructural characterisation and in vitro apatite formationof CaO-P 2O 5-TiO 2-MgO-Na 2O glass-ceramics (2001) J. Eur. Ceram. Soc, 21 (2), pp. 169-175; Rehman, I., Bonfield, W., Characterization of hydroxyapatite and carbonated apatite by photo acoustic FTIR spectroscopy (1997) J. Mater. Sci.-Mater. Med, 8 (1), pp. 1-4; Farrow, L.A., Vogel, E.M., (1992) J. Non-Crystal. Solids, 143, p. 59; Li, Y., (2003) J. Chin. Ceram. Soc, 31, p. 669. , in Chinese; Hudgens, J.J., Martin, S.W., (1993) J. Am. Ceram. Soc, 76, p. 1691; Brow, R.K., Tallant, D.R., Myers, S.T., Phifer, C.C., (1995) J. Non-Crystal. Solids, 191, p. 45; Bobovish, Y.S., (1962) Opt. Spect. (English Transl.), 13, p. 274; Nelson Jr, L.S., Amorphous calcium phosphates of different composition give very similar EXAFS spectra (1989) Phys. B: Cond. Matter, 158 (1-3), pp. 105-106; Stranford, T.C., Condrate, R.A., Cornilsen, B.C., (1981) J. Molec. Struct, 73, p. 231; Wazer, J.R.V., (1958) Phosphorus and its Compounds, 1. , Interscience, New York; Brow, R.K., (1994) J. Non-Crysl. Solids, 177, p. 221; Tatsumisago, M., Kowada, Y., Minami, T., (1988) Phys. Chem. Glasses, 29, p. 63; Meyer, K., (1998) Phys. Chem. Glasses, 39, p. 108; Ed., J. A. D. Lange's Handbook of Chemistry, Third edition, McGraw-Hill Book Company, 1985. p. 3-117, p3-123Iwamoto, N., (1986) Yogyo-Kyokai-Shi, 94, p. 856. , in Japanese

Synthesis and cytocompatibility of porous chitosan-silicate hybrids for tissue engineering scaffold application - Shirosaki, Y.; Okayama, T.; Tsuru, K.; Hayakawa, S.; Osaka, A. (Chemical Engineering JournalChem. Eng. J., 2008)
Chitosan-silicate hybrids with 3D porous structures were prepared with freeze-drying precursor solutions derived from chitosan and γ-glycidoxypropyltrimethoxysilane (GPTMS). They were formed easily in any shape, such as sheets, pellets, disks, granules, and even roll-cakes. The pore size was strongly dependent on the freezing temperature: lower freezing temperature resulted smaller pores, about 110 μm for the hybrids frozen at -20 °C, and about 50 μm for those at -85 °C. The pore size was little dependent on the GPTMS content. In contrast, the GPTMS content affected porosity a littlie: ∼80% for chitosan, and ∼90% for the GPTMS-containing hybrids. Thus, their porous microstructure was controllable due to the freezing temperature and composition. MG63 osteoblastic cells were cultured up to 7 days on the porous hybrids. The cells adhered on the pore walls, proliferated, and migrated deep into the pore structure. It was thus concluded that the present chitosan-silicate hybrids were promising for tissue engineering scaffold applications. © 2007 Elsevier B.V. All rights reserved.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: CMEJAdoi: 10.1016/j.cej.2007.10.012Language of Original Document: EnglishCorrespondence Address: Osaka, A.; Graduate School of Natural Science and Technology, Okayama University, Okayama, 700-8530, Japan; email: osaka@cc.okayama-u.ac.jpReferences: Tateishi, T., Chen, G., Ushida, T., Biodegradable porous scaffolds for tissue engineering (2002) J. Artif. Organs, 5, pp. 77-83;Lee, Y.-K., Mooney, J.D., Hydrogels for tissue engineering (2001) Chem. Rev., 101, pp. 1869-1879; Park, S.-N., Park, J.-C., Kim, H.-O., Song, M.-J., Suh, H., Characterization of porous collagne/hyaluronic acid scaffold modified by 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide cross-linking (2002) Biomaterials, 23, pp. 1205-1212; Kuo, C.-K., Ma, P.-X., Ionically crosslinked alginate hydrogels as scaffolds for tissue engineering: Part 1. Structure, gelation rate and mechanical properties (2001) Biomaterials, 22, pp. 511-521; Widmer, M.S., Gupta, P.K., Lu, L., Meszlenyi, R.K., Evans, G.R.D., Brandt, K., Savel, T., Mikos, A.G., Manufacture of porous biodegradable polymer conduits by an extrusion process for guided tissue regeneration (1998) Biomaterials, 19, pp. 1945-1955; Wang, Y.-C., Lin, M.-C., Wang, D.-M., Hsieh, H.-J., Fabrication of a novel porous PGA-chitosan hybrid matrix for tissue engineering (2003) Biomaterials, 24, pp. 1047-1057; Park, Y.-J., Lee, M.-Y., Lee, J.-Y., Seol, Y.-J., Chung, C.-P., Lee, S.-J., Controlled release of platelet-derived growth factor-BB from chondroitin sulfate-chitosan sponge for guided bone regeneration (2000) J. Control. Release, 67, pp. 385-394; Lee, J.-Y., Nam, S.-H., Im, S.-Y., Park, Y.-J., Lee, Y.-M., Seol, Y.-J., Chung, C.-P., Lee, S.-J., Enhanced bone formation by controlled growth factor delivery from chitosan-based biomaterials (2002) J. Control. Release, 78, pp. 187-197; Wan, Y., Wu, H., Wen, D., Porous-conductive chitosan scaffolds for tissue engineering: 1. Preparation and characterization (2004) Macromol. Biosci., 4, pp. 882-890; Li, J., Pan, J., Zhang, L., Guo, X., Yu, Y., Culture of primary rat hepatocytes within porous chitosan scaffolds (2003) J. Biomed. Mater. Res., 67 A, pp. 938-943; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Sol-gel preparation and in vitro deposition of apatite on porous gelatin-siloxane hybrids (2001) J. Non-Cryst. Solid, 285, pp. 116-122; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Novel approach to fabricate porous gelatin-siloxane hybrids for bone tissue engineering (2002) Biomaterials, 23, pp. 4765-4773; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., In vitro cytocompatibility of MG63 cells on chitosan-organosiloxane hybrids membranes (2005) Biomaterials, 26, pp. 485-493; Hua, H., Jie, W., Changshengh, L., Development of asymmetric gradational-changed porous chitosan membrane for guided periodontal tissue regeneration (2007) Compos. B, 38, pp. 311-316; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-5911; Kang, H.-W., Tabata, Y., Ikada, Y., Fabrication of porous gelatin scaffolds for tissue engineering (1999) Biomaterials, 20, pp. 1339-1344; Ho, M.-H., Kuo, P.-Y., Hsieh, H.-J., Hsien, T.-Y., Hou, L.-T., Lai, J.-Y., Wang, D.-M., Preparation of porous scaffolds by using freeze-extraction and freeze-gelation methods (2004) Biomaterials, 25, pp. 129-138
Keywords: chitosan; Cytocompatibility; GPTMS; Organic-inorganic hybrid; Osteoblastic cell MG63; Osteoblasts; Pore size; Pore structure; Scaffold; Silicates; Tissue engineering; γ-Glycidoxypropyltrimethoxysilane (GPTMS)

Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation - Amaral, I.F.; Cordeiro, A.L.; Sampaio, P.; Barbosa, M.A. (Journal of Biomaterials Science, Polymer EditionJ. Biomater. Sci. Polym. Ed., 2007)
Chitosan (Ch) is being actively investigated as a non-protein template for the growth of an increasing number of anchorage-dependent cells, including chondrocytes and bone cells. In the present work, Ch films with degrees of N-acetylation (DAs) in the range of 4 to 49% were evaluated with respect to the attachment, spreading and short-term proliferation of osteoblasts, using human osteoblastic MG-63 cells. The films were characterized in terms of surface morphology and surface charge by atomic force microscopy and streaming potential measurements, respectively. Cell attachment was assessed after 3 and 24 h of cell culture. After 24 h of incubation, cell attachment was found to be dependent on the DA, lower DAs favouring cell adhesion. With time, cell spreading and cytoskeleton organization were only attained for DAs ≤ 13%. Regarding cell proliferation, cells grown on films with the lowest DA (4%) revealed a higher specific growth rate as compared to those grown on films with higher DAs. Films with a DA of 49% failed to sustain cell proliferation. In addition, a longer lag-phase was observed on Ch, as compared to TCPS, in accordance to an observed delay of cell spreading. The present findings revealed that differences in the DA as small as 9% may be critical in terms of the osteoblast response to two-dimensional Ch-based matrices. © 2007 VSP.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JBSEEdoi: 10.1163/156856207780425068Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; Biocompatible Materials; Chitosan, 9012-76-4References: Vacanti, C.A., Bonassar, L.J., Vacanti, J.P., (2000) Principles of Tissue Engineering, p. 671. , R. P. Lanza, R. Langer and J. Vacanti Eds, p, Academic Press, San Diego, CA;Bruder, S.P., Caplan, A.I., (2000) Principles of Tissue Engineering, p. 683. , R. P. Lanza, R. Langer and J. Vacanti Eds, p, Academic Press, San Diego, CA; Burg, K.J.L., Porter, S., Kellam, J.F., (2000) Biomaterials, 21, p. 2347; Khor, E., Lim, L.Y., (2003) Biomaterials, 24, p. 2339; Nettles, D.L., Elder, S.H., Gilbert, J.A., (2002) Tissue Eng, 8, p. 1009; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., (2002) J. Control. Rel, 78, p. 187; Muzzarelli, R.A.A., (1997) Cell. Mol. Life Sci, 53, p. 131; Madihally, S.V., Matthew, H.W.T., (1999) Biomaterials, 20, p. 1133; Chupa, J.M., Foster, A.M., Sumner, S.R., Madihally, S.V., Matthew, H.W.T., (2000) Biomaterials, 21, p. 2315; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., (2000) J. Biomed. Mater. Res, 51, p. 586; Ho, M.H., Wang, D.M., Hsieh, H.J., Liu, H.C., Hsien, T.Y., Lai, J.Y., Hou, L.T., (2005) Biomaterials, 26, p. 3197; A. Domard, in: Advances in Chitin Science, II, A. Domard, G. A. F. Roberts and K. M. Varum (Eds), p. 410. Jacques André, Lyon (1997)Tomihata, K., Ikada, Y., (1997) Biomaterials, 18, p. 567; Baxter, A., Dillon, M., Taylor, K.D.A., Roberts, G.A.F., (1992) Int. J. Biol. Macromol, 14, p. 166; Anselme, K., (2000) Biomaterials, 21, p. 667; Prasitsilp, M., Jenwithisuk, R., Kongsuwan, K., Damrongchai, N., Watts, P., (2000) J. Mater. Sci. Mater. Med, 11, p. 773; Chatelet, C., Damour, O., Domard, A., (2001) Biomaterials, 22, p. 261; Dhiman, H.K., Ray, A.R., Panda, A.K., (2004) Biomaterials, 25, p. 5147; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., (2001) Polymer, 42, p. 3569; Mima, S., Miya, M., Iwamoto, R., Yoshikawa, S., (1983) J. Appl. Polym. Sci, 28, p. 1909; Aiba, S., (1986) Int. J. Biol. Macromol, 8, p. 173; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., (1996) Carbohydr. Polym, 29, p. 63; (1987) Guideline on Validation of the Limulus Amebocyte Lysate Test as an End-product Endotoxin Test for Human and Animal Parental Drugs, Biological Products, and Medical Devices, , US Department of Health and Human Services, Public Health Service, Food and Drug Administration, US Department of Health and Human Services, Washington, DC; Nakagawa, Y., Murai, T., Hasegawa, C., Hirata, M., Tsuchiya, T., Yagami, T., Haishima, Y., (2003) J. Biomed. Mater. Res, 66 B, p. 347; Walker, S.L., Bhattacharjee, S., Hoek, E.M.V., Elimelech, M., (2002) Langmuir, 18, p. 2193; Clover, J., Gowen, M., (1994) Bone, 15, p. 585; Mosmann, T., (1983) J. Immunol. Methods, 65, p. 55; Domke, J., Dannohl, S., Parak, W.J., Muller, O., Aicher, W.K., Radmacher, M., (2000) Colloid Surfaces B: Biointerfaces, 19, p. 367; Sorlier, P., Denuziere, A., Viton, C., Domard, A., (2001) Biomacromolecules, 2, p. 765; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., (2005) J. Biomed. Mater. Res, 75 A, p. 387; Andrade, J.D., Smith, L.M., Gregonis, D.E., (1985) Surface and Interfacial Aspects of Biomedical Polymers, 1, p. 249. , J. D. Andrade Ed, p, Plenum Press, New York, NY; Dewez, J.L., Doren, A., Schneider, Y.J., Rouxhet, P.G., (1999) Biomaterials, 20, p. 547; Kikuchi, T., Yoshikai, Y., Miyoshi, J., Katsuki, M., Musikacharoen, T., Mitani, A., Tanaka, S., Matsuguchi, T., (2003) J. Dent. Res, 82, p. 546; Denuziere, A., Ferrier, D., Damour, O., Domard, A., (1998) Biomaterials, 19, p. 1275; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2005) Biomaterials, 26, p. 485; Wang, J.H., Wei, C.W., Liu, H.C., Young, T.H., (2003) J. Biomed. Mater. Res, 64 A, p. 606; Michael, K.E., Vernekar, V.N., Keselowsky, B.G., Meredith, J.C., Latour, R.A., Garcia, A.J., (2003) Langmuir, 19, p. 8033; Keselowsky, B.G., Collard, D.M., Garcia, A.J., (2003) J. Biomed. Mater. Res, 66 A, p. 247; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., (2003) J. Biomed. Mater. Res, 67 A, p. 538; McFarland, C.D., Mayer, S., Scotchford, C., Dalton, B.A., Steele, J.G., Downes, S., (1999) J. Biomed. Mater. Res, 44, p. 1; Cowles, E.A., Brailey, L.L., Gronowicz, G.A., (2000) J. Biomed. Mater. Res, 52, p. 725; Marco, R.A.W., Diaz-Montero, C.M., Wygant, J.N., Kleinerman, E.S., McIntyre, B.W., (2003) J. Cell. Biochem, 88, p. 1038; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Dean, D.D., Boyan, B.D., (1995) J. Biomed. Mater. Res, 29, p. 389; Anselme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Iost, A., Hardouin, P., (2000) J. Biomed. Mater. Res, 49, p. 155; Zinger, O., Anselme, K., Denzer, A., Habersetzer, P., Wieland, M., Jeanfils, J., Hardouin, P., Landolt, D., (2004) Biomaterials, 25, p. 2695
Keywords: Acetylation; AFM; article; Atomic force microscopy; Biocompatible Materials; biofilm; Biofilms; biomaterial; bone cell; cartilage cell; cell adhesion; cell anchorage; Cell culture; cell growth; Cell Line, Tumor; cell proliferation; Cell Shape; cell spreading; cell survival; Chemical structure; chemistry; Chitin; chitosan; comparative study; controlled study; cytoskeleton; Degree of acetylation; drug effect; Growth kinetics; human; human cell; Humans; incubation time; metabolism; Microscopy, Atomic Force; osteoblast; Osteoblast-like cells; Osteoblasts; Pathology; priority journal; Surface charge; Surface Properties; surface property; Surface treatment; tumor cell line; Zeta potential

Degradation studies of some polymeric biomaterials: Polypropylene PP and polyvinylidene difluoride (PVDF) - Silva, R.A.; Silva, P.A.; Carvalho, M.E. (Materials Science ForumMater Sci Forum, 2007)
Degradation studies of PP and PVDF monofilaments were carried out using a special chamber for several periods of time. One set of the samples was exposed to a 0.9 % NaCl solution and to ultraviolet radiation at 83° C and the other set involved the exposition in air under the same conditions of irradiation and temperature. Scanning Electron Microscopy (SEM) analysis showed direct evidence of PP degradation. Meanwhile, the PVDF monofilaments showed no apparent evidence of degradation under the same conditions. Differential Thermal Analysis (DTA) curves, FTIR spectra and Oxidation Induction Time experiments confirmed the results of SEM Analysis.
Conference code: 71122Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: MSFOELanguage of Original Document: EnglishCorrespondence Address: Silva, R.A.; Instituto Superior de Engenharia do Porto, Rua Dr. António Bernardino de Almeida, 431, 4200-072 Porto, Portugal; email: rasilva@isep.ipp.ptReferences: Kurosaki, S., Otsuka, H., Kunitomo, M., Koiama, M., Pawankar, R., Matumoto, K., (1999) J. Nippon. Med. Sch, 66, pp. 41-44;Salthouse, T.N., Biocompatibility of Sutures (1982) Biocompatibility in Clinical Practice, 1, pp. 11-33. , D. F. Williams ed, Boca Raton, FL: CRC Press Inc; Craig, P.A., Williams, I.A., Magoun, A.D., Levin, A.J., Bogdansky, S., Jones, J.P., (1975) Surg. Gynecol. Obstet, 141, pp. 1-8; D. F. Williams. Corrosion and Degradation of implant Materials, B. C. Syrett, A. Acharya, eds. STP 684, Philadelphia, PA: ASTM Special Technical Publication, (1978) 61-75Dahlke, H., Docia, N., Thurran, K., (1980) J. Biomed. Mater. Res, 14, pp. 51-68; Postlethwait, R.W., (1975) Ann. Sur, 190, pp. 127-132; Salthouse, T.N., Matlaga, B.F., (1985) J. Surg. Res, 19, pp. 127-132; Alaymo, F., Vacarri, M., (1985) Ann. Thoracic. Surg, 39, pp. 400-404; Cornel, G., (1982) Ann. Thoracic. Surg, 33, pp. 64-67; Kawai, H., (1969) Jpn. J. Appl. Phys, 8, pp. 975-976; Bergman Jr., J.G., Mcfee, J.H., Crane, G.R., (1971) Appl. Phys. Lett, 18, pp. 203-205; Xiao, D.Q., Lang, S.B., (1989) IEEE Trans. Elec. Insul, 24, pp. 503-516; Ganz, B., (1989) IEEE Trans. Elec. Insul, 24, pp. 499-502; Laroche, G., Marois, Y., Guidoin, R., King, M., Martin, L., How, T., Douville, Y., (1995) J. Biomed. Mater. Res, 29, pp. 1525-1536; Ademovic, Z., Klee, D., Kingshott, P., Kaufman, R., Hocker, H., (2002) Biomolecular Engineering, 19, pp. 277-182; Klee, D., Ademovic, Z., Bosserhoff, A., Hocker, H., Maziolis, G., Erli, H.-J., (2003) Biomaterials, 24, pp. 3663-3670; Wada, A., Kubota, H., Hatanaka, H., Miura, H., Iwamoto, Y., (2001) J. Hand Surg, 26 B, pp. 212-216; Klinge, U., Klosterhalfen, B., Hottinger, A.P., Junge, K., Schumpelick, V., (2002) Biomaterials, 23, pp. 3487-3493
Keywords: Biomaterials; Degradation; Degradation of polypropylene and polyvinylidene difiuoride; Fourier transform infrared spectroscopy; FTIR spectroscopy; Monofilament sutures; Monofilaments; Oxidation induction time; Polypropylenes; Redox reactions; Thermal analysis; Thermoanalysis

A Gait Analysis Laboratory for rehabilitation of patients with musculoskeletal impairments - Sousa, D.S.S.; Tavares, J.M.R.S.; Correia, M.V.; Barbosa, J.G.; Chã, C.V.; Mendes, E. (Proceedings of the International Symposium CompIMAGE 2006 - Computational Modelling of Objects Represented in Images: Fundamentals, Methods and ApplicationsProc. Int. Symp. CompIMAGE - Comput. Model. Objects Represent. Images: Fundam., Methods Appl., 2007)
This paper describes the technology (software & hardware) used in the Gait Analysis Laboratory of CRPG - Centro de Reabilitação Projissional de Gaia. This laboratory is mainly intended to support CRPG with quantitative data for clinical rehabilitation of patients with musculoskeletal pathologies, namely in the lower limbs. Usually, for the gait analysis is considered data obtained from several acquisition sensors, such as: image cameras, electromyographic devices, pressure devices and force plates. This paper also presents briefly how quantitative motion analysis can be used for a clinical point of view and it presents the influence of image algorithms in gait rehabilitation. © 2007 Taylor & Francis Group.
Conference code: 75470Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Sousa, D. S. S.; INEGI, Instituto de Engenharia Mecǎnica e Gestão Industrial, Porto, PortugalReferences: Baker, R., Gait analysis methods in rehabilitation (2006) Journal of Neuro Engineering and Rehabilitation, 3 (1), p. 4;Cappozzo, A., Delia Croce, U., Human movement analysis using stereophotogrammetry. Part I: Theoretical background (2005) Gait & Posture, 21, pp. 186-196; Chau, T., A review of analytical techniques for gait data. Part 1: Fuzzy, statistical and fractal methods (2001) Gait & Posture, 13 (1), pp. 49-66; Davis, R.B., Reflections on clinical gait analysis (1997) Journal of Electromyography and Kinesiology, 7 (4), pp. 251-257; Davis III, R.B., Clinical gait analysis (1988) Engineering in Medicine and Biology Magazine, IEEE, 7 (3), pp. 35-40; Figueroa, P.J., Leite, N.J., A flexible software for tracking of markers used in human motion analysis (2003) Computer Methods and Programs in Biomedicine, 72, pp. 155-165; Gavrila, D., The visual analysis of human movement: A survey (1999) Computer Vision and Image Understanding, 73 (1), pp. 82-98; Merletti, R., Parker, P., (2004) Electromyography: Physiology, engineering and noninvasive applications, , Wiley-IEEE Press; (1978) NASA Reference Publication, , NASA, Springfield: NASA; Orlin, M., McPoil, T., Plantar pressure assessment (2000) Physical therapy, 80 (4), pp. 399-409; Perry, J., The contribution of dynamic electromyography to gait analysis (1998) Monograph 002: Gait analysis in the science of rehabilitation. 1998, , J. DeLisa ed, Washington, DC; Pinho, R., Tavares, J., A Movement Tracking Management Model with Kalman Filtering, Global Optimization Techniques and Mahalanobis Distance (2005) ICCMSE 2005 - International Conference of Computational Methods in Sciences and Engineering; Loutraki, 21-26 October 2005, , Korinthos: Greece; Pinho, R., Tavares, J., Human Movement Tracking and Analysis with Kalman Filtering and Global Optimization Techniques (2005) ICCB2005 - II International Conference on Computational Bioengineering; Instituto Superior Técnico, Lisboa, 14-16 September 2005, , Lisboa: Portugal; Rosenbaum, D., Becker, H., Plantar pressure distribution measurements. Technical background and clinical applications (1997) Foot and Ankle Surgery, 3 (1), pp. 1-14; Roy, K., Force, pressure and motion measurements in the foot: Current concepts (1988) Clinics in Podiatric Medicine and Surgery, 5, pp. 491-508; Schmalz, T., Blumentrit, S., Energy expenditure and biomechanical characteristics of lower limb amputee gait: The influence of prosthetic alignment and different prosthetic components (2002) Gait & Posture, 16, pp. 255-263; Shabana, A., (2001) Computational Dynamics, , NY: John Wiley; Sisto, S. 1998. An overview of the value of information resulting from instrumented gait analysis for the physical therapist. In J. DeLisa (ed.) Monograph 002: Gait analysis in the science of rehabilitation. 1998. Washington, DC. Sutherland, D. 2001. The evolution of clinical gait analysis part 1: kinesiological EMG. Gait & Posture 14(1): 61-70Sutherland, D., The evolution of clinical gait analysis: Part II Kinematics (2002) Gait & Posture, 16 (2), pp. 159-179; Tavares, J., Bastos, L., Improvement of Modal Matching Image Objects in Dynamic Pedobarography using Optimization Techniques (2005) Electronic Letters on Computer Vision and Image Analysis, special issue on Articuled Motion & Deformable Objects, 5, pp. 1-20; Tavares, J., Barbosa, J., Matching Image Objects in Dynamic Pedobarography (2000) RecPad 2000 - 11th Portuguese Conference on Pattern Recognition; Porto, 11-12 Maio 2000, , Porto, Portugal; Urry, S., Plantar pressure-measurement sensors (1999) Measurement Science and Technology, 10, pp. 16-32; Whittle, M., Clinical gait analysis: A review (1996) Human Movement Science, 15, pp. 369-387; Whittle, M., (2003) Gait analysis an introduction, , Oxford, Boston: Butterworth-Heinemann; Winter, D., (2005) Biomechanics and motor control of human movement, , Hoboken: John Wiley & Sons
Keywords: Acquisition sensors; Electromyographic; Force plates; Gait analysis; Gait rehabilitations; Image algorithms; Lower limbs; Motion analysis; Patient rehabilitation; Pressure devices; Quantitative datum

Nanohydroxyapatite microspheres as delivery system for antibiotics: Release kinetics, antimicrobial activity, and interaction with osteoblasts - Ferraz, M.P.; Mateus, A.Y.; Sousa, J.C.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2007)
Severe periodontitis treatment, where massive alveolar bone loss occurs, involves bone defect filling and intensive systemic log-term antibiotics administration. This study aims at developing novel injectable drug delivery systems (nanohydroxyapatite microspheres) with the drug releasing capability for periodontitis treatment and simultaneously initiating the osteointegration process. Materials were characterized by XRD, SEM, inverted stand optical microscope analysis, and mercury porosimetry method. Amoxicillin, amoxicillin + clavulanic acid, and erythromycin were the antibiotics used. Release properties during 28 days from the hydroxyapatite (HA) granules, and two types of nanoHA microspheres were investigated. Biocompatibility was assessed by cytotoxicity assays. HA granules were inadequate, releasing all antibiotic during the first hours. The concentration of antibiotics released in the first days from HA-2 was higher than from HA-1 microspheres, because of the increased porosity and surface area. The release profiles (fast initial release followed by long-term sustained release) of effective doses of antibiotics make these systems good alternatives for antibiotics delivery. Osteoblasts proliferated well on both types of microspheres, being cell growth enhanced in the presence of antibiotics. Erythromycin presented the most beneficial effect. Combining the sustained antibiotic release with the osteoconduction, resorbability, and potential use as injectable bone filling material of porous HA microspheres, these systems provided a forth fold beneficial effect. © 2007 Wiley Periodicals, Inc.
Cited By (since 1996): 32Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31151PubMed ID: 17252559Language of Original Document: EnglishCorrespondence Address: Ferraz, M.P.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: mpferraz@ufp.ptChemicals/CAS: amoxicillin, 26787-78-0, 34642-77-8, 61336-70-7; amoxicillin plus clavulanic acid, 74469-00-4, 79198-29-1; clindamycin, 18323-44-9; erythromycin, 114-07-8, 70536-18-4; hydroxyapatite, 1306-06-5, 51198-94-8; metronidazole, 39322-38-8, 443-48-1; minocycline, 10118-90-8, 11006-27-2, 13614-98-7; tetracycline, 23843-90-5, 60-54-8, 64-75-5; Anti-Bacterial Agents; Durapatite, 1306-06-5References: Krejci, C.B., Bissada, N.F., Farah, C., Greenwell, H., Clinical-evaluation of porous and nonporous hydroxyapatite in the treatment of human periodontal bony defects (1987) J Periodontol, 58, pp. 521-528;Kinane, D.F., Lindhe, J., Pathogenesis of periodontitis (2002) Clinical Periodontology and Implant Dentistry, pp. 189-225. , Lindhe J, Karring T, Lang NP, editors, Copenhagen: Munksgaard;; Slots, J., Armitage, G.C., Cochran, D., Cohen, R.E., Greenstein, G., Mariotti, A., Rethman, M.P., and others, Systemic antibiotics in periodontics (1996) J Periodontol, 67, pp. 831-838; Mombelli, A., Antibiotics in periodontal therapy (2002) Clinical Periodontology and Implant Dentistry, , Lindhe J, Karring T, Lang NP, editors, Copenhagen: Munksgaard;; Etienne, D., Locally delivered antimicrobials for the treatment of chronic periodontitis (2003) Oral Dis, 9, pp. 45-50; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Porous HA scaffolds for drug releasing (2005) Bioceramics, 17, pp. 407-410; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., Porous hydroxyapatite and glass reinforced hydroxyapatite for controlled release of sodium ampicillin (2004) Bioceramics, 16, pp. 997-1000; Hannes, P.J., Purvis, J.P., Local anti-infective therapy: Pharmacological agents. A systemic review (2003) Ann Periodontol, 8, pp. 79-98; Soskolne, W.A., Heasman, P.A., Stabholz, A., Smart, G.J., Palmer, M., Flashner, M., Newman, H.N., Sustained local delivery of chlorhexidine in the treatment of periodontitis: A multi-center study (1997) J Periodontol, 68, pp. 32-38; Greenstein, G., Polson, A., The role of local drug delivery in the management of periodontal diseases: A comprehensive review (1998) J Periodontol, 69, pp. 507-520; Killoy, W.J., Chemical treatment of periodontitis: Local delivery of antimicrobials (1998) Int Dent J, 48, pp. 305-315; Schwach-Abdellaoui, K., Vivien-Castioni, N., Gurny, R., Local delivery of antimicrobial agents for the treatment of periodontal diseases (2000) Eur J Pharm Biopharm, 50, pp. 83-99; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Development of a system to adsorb drugs onto calcium phosphate materials (2005) J Mater Sci-Mater Med, 16, pp. 641-646; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Adsorption isotherm of sodium ampicillin onto dense and porous hydroxyapatite (2005) Bioceramics, 17, pp. 387-390; Queiroz, A.C., Santos, J.D., Monteiro, F.J., da Silva, MHP dissolution studies of hydroxyapatite and glass-reinforced hydroxyapatite ceramics (2003) Mater Char, 50, pp. 197-202; Rauschmann, M.A., Wichelhaus, T.A., Stirnal, V., Dingeldein, E., Zichner, L., Schnettler, R., Alt, V., Nanocrystalline hydroxyapatite and calcium sulphate as biodegradable composite carrier material for local delivery of antibiotics in bone infections (2005) Biomaterials, 26, pp. 2677-2684; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., Production of porus hydroxyapatite with potential for controlled drug delivery (2004) Mater Sci Forum, 455-456, pp. 358-360; Daculsi, G., Passuti, N., Effect of the macroporosity for osseous substitution of calcium-phosphate ceramics (1990) Biomaterials, 11, pp. 86-87; Gauthier, O., Bouler, J.M., Weiss, P., Bosco, J., Daculsi, G., Aguado, E., Kinetic study of bone ingrowth and ceramic resorption associated with the implantation of different injectable calcium-phosphate bone substitutes (1999) J Biomed Mater Res, 47, pp. 28-35; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Specific proteins mediate enhanced osteoblast adhesion on nanophase ceramics (2000) J Biomed Mater Res, 51, pp. 475-483; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21, pp. 1803-1810; Webster, T.J., Siegel, R.W., Bizios, R., Enhanced surface and mechanical properties of nanophase ceramics to achieve orthopaedic/dental implant efficacy (2000) Bioceramics, 13, pp. 321-324; Liou, S.C., Chen, S.Y., Liu, D.M., Synthesis and characterization of needlelike apatitic nanocomposite with controlled aspect ratios (2003) Biomaterials, 24, pp. 3981-3988; Ferraz, M.P., Monteiro, F.J., Manuel, C.D., Hydroxyapatite nanoparticles: A review of preparation methodologies (2004) J Appl Biomater Biomech, 2, pp. 74-80; Barrias CC, Ribeiro CC, Martins MCL, Barbosa MA, Rodrigues D, Miranda MCS. Calcium phosphate microspheres for localised delivery of a therapeutic enzyme. Bioceramics 2006;18 (Parts 1/2):903-906Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Calcium phosphate-alginate microspheres as enzyme delivery matrices (2004) Biomaterials, 25, pp. 4363-4373; Socransky, S.S., Haffajee, A.D., Microbiology of periodontal disease (2002) Clinical Periodontology and Implant Dentistry, , Lindhe J, editor, Copenhagen: Munksgaard;; Slots, J., Selection of antimicrobial agents in periodontal therapy (2002) J Periodontal Res, 37, pp. 389-398; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Preparation and characterisation of calcium-phosphate porous microspheres with a uniform size for biomedical applications (2006) J Mater Sci-Mater Med, 17, pp. 455-463; Barrias, C.C., Ribeiro, C.C., Lamghari, M., Sá, C., Barbosa, M.A., Proliferation, activity and osteogenic differentiation of bone marrow stromal cells cultured on calcium titanium phosphate microspheres (2005) J Biomed Mater Res A, 72, pp. 57-66; Mateus, A.Y.P., Ferraz, M.P., Monteiro, F.J., Comparative study of injectable material synthesised from alginate and two types of hydroxyapatite Submitted for publicationFerraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P2O5 glass hydroxyapatite double layer plasma sprayed coatings: In vitro bioactivity evaluation (1999) J Biomed Mater Res, 45, pp. 376-383; Hyakuna, K., Yamamuro, T., Kotoura, Y., Oka, M., Nakamura, T., Kitsogi, T., Kokubo, T., Kushitani, H., Surface reactions of calcium phosphate ceramics to various solutions (1990) J Biomed Mater Res, 24, pp. 471-488; Gautier, H., Daculsi, G., Merle, C., Association of vancomycin and calcium phosphate by dynamic compaction: In vitro characterization and microbiological activity (2001) Biomaterials, 22, pp. 2481-2487; Kimakhe, S., Bohic, S., Larrose, C., Reynaud, A., Pilet, P., Giumelli, B., Heymann, D., Daculsi, G., Biological activities of sustained polymyxin B release from calcium phosphate biomaterial prepared by dynamic compaction: An in vitro study (1999) J Biomed Mater Res, 47, pp. 18-27; Korkusuz, F., Uchida, A., Shinto, Y., Araki, N., Inoue, K., Ono, K., Experimental implant-related osteomyelitis treated by antibiotic-calcium hydroxyapatite ceramic composites (1993) J Bone Joint Surg-Br, 75, pp. 111-114; Otsuka, M., Matsuda, Y., Kokubo, T., Yoshihara, S., Nakamura, T., Yamamuro, T., A novel skeletal drug-delivery system using self-setting bioactive glass bone-cement. II. Drug-release from a novel self-setting bioactive glass bone-cement containing cephalexin and its physicochemical properties (1995) J Biomed Mater Res, 29, pp. 33-38; Shinto, Y., Uchida, A., Korkusuz, F., Araki, N., Ono, K., Calcium hydroxyapatite ceramic used as a delivery system for antibiotics (1992) J Bone Joint Surg Br, 74, pp. 600-604; Yamamura, K., Iwata, H., Yotsuyanagi, T., Synthesis of antibiotic-loaded hydroxyapatite beads and invitro drug release testing (1992) J Biomed Mater Res, 26, pp. 1053-1064; Clover, J., Gowen, M., Are Mg-63 and Hos Te85 human osteosarcoma cell-lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591
Keywords: alveolar bone; amoxicillin; amoxicillin plus clavulanic acid; Anti-Bacterial Agents; Antibacterial; antibiotic agent; antibiotic resistance; Antibiotics administration; antimicrobial activity; article; Bacteria; Cell Communication; Cell Death; cell growth; cell kinetics; Cell Line; cell proliferation; clindamycin; concentration response; controlled study; Cytotoxicity; Drug delivery; drug delivery system; Drug Delivery Systems; Drug release; Durapatite; erythromycin; Escherichia coli; human; human cell; Humans; hydroxyapatite; Kinetics; materials testing; metronidazole; Microbial Sensitivity Tests; microsphere; Microspheres; minocycline; Nanohydroxyapatite; nanoparticle; nanoparticles; nonhuman; Optical microscope analysis; osteoblast; Osteoblasts; osteolysis; periodontitis; porosity; Staphylococcus aureus; surface property; sustained drug release; Tetracycline; unclassified drug; X ray diffraction

A novel dry active electrode for EEG recording - Fonseca, C.; Silva Cunha, J.P.; Martins, R.E.; Ferreira, V.M.; Marques De Sá, J.P.; Barbosa, M.A.; Martins Da Silva, A. (IEEE Transactions on Biomedical EngineeringIEEE Trans. Biomed. Eng., 2007)
The design and testing of a "dry" active electrode for electroencephalographic recording is described. A comparative study between the EEG signals recorded in human volunteers simultaneously with the classical Ag-AgCl and "dry" active electrodes was carried out and the reported preliminary results are consistent with a better performance of these devices over the conventional Ag-AgCl electrodes. © 2007 IEEE.
Cited By (since 1996): 24Export Date: 21 November 2012Source: ScopusArt. No.: 23CODEN: IEBEAdoi: 10.1109/TBME.2006.884649PubMed ID: 17260869Language of Original Document: EnglishCorrespondence Address: Fonseca, C.; INEB Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Universidade Do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cfonseca@ibmc.up.ptChemicals/CAS: Biocompatible Materials; Titanium, 7440-32-6; titanium dioxide, 13463-67-7References: Portnoy, W., David, R., Akers, L., Insulated ECG electrodes (1974) Biomedical Electrode Technology, , H. A. Miller and D. C. Harrison, Eds. New York: Academic;Nishimura, S., Tomita, Y., Horiuchi, T., Clinical application of an active electrode using an operational amplifier (1992) IEEE Trans. Biomed. Eng, 39 (10), pp. 1090-1099. , Oct; Taheri, A., Knight, R., Smith, R., A dry electrode for EEG recording (1994) Electroencephalogr. Clin. Neurophysiol, 90, pp. 376-383; Searle, A., Kirkup, L., A direct comparison of wet, dry and insulating bioelectric recording electrodes (2000) Physiol. Meas, 22, pp. 71-83; Fonseca, C., Vaz, F., Barbosa, M.A., Electrochemical behaviour of titanium coated stainless steel by R.F. sputtering in synthetic sweat solutions for electrode applications (2004) Corrosion Sci, 46 (12), pp. 3005-3018; Matsuo, T., IInuma, K., Esashi, M., Barium titanate ceramics capacitive type EEG elecrode (1973) IEEE Trans. Biomed. Eng, BME-20, pp. 299-300; Perez, J., Vilarinho, P., Kholkin, A., High-quality Pbzr0.52Ti0. 48O3 films prepared by modified sol-gel route at low temperature (2004) Thin Solid Films, 449 (1-2), pp. 20-24; Rosell, J., Colominas, J., Riu, P., Pallas-Areny, R., Webster, J., Skin impedance from 1 Hz to 1 MHz (1988) IEEE Trans. Biomed. Eng, 35 (8), pp. 649-651. , Aug; Ferree, T., Luu, P., Russell, G., Tucker, D., Scalp electrode impedance, infection risk and EEG data quality (2001) Clin. Neurophysiol, 112 (3), pp. 536-544
Keywords: article; Biocompatible Materials; Bioelectric phenomena; Bioelectric signal recording; bioenergy; biomedical electrodes; Biomedical engineering; Data recording; Dry electrodes; Electric Impedance; Electrochemical electrodes; electrode; Electrodes; electroencephalogram; Electroencephalographic recording; electroencephalography; Equipment Design; Equipment Failure Analysis; Feasibility Studies; Pilot Projects; signal transduction; Silver compounds; Titanium

Opening wedge high tibial osteotomy using 3D biomodelling Bonelike® macroporous structures: Case report - Gutierres, M.; Dias, A.G.; Lopes, M.A.; Hussain, N.S.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2007)
Two synthetic calcium phosphates in porous wedge shape, Bonelike® and a commercial HA/β-TCP biphasic material, were used as an alternative to bone autografts and allografts in the treatment of medial compartment osteoarthritis of varus knees. The structure of Bonelike® has a 3D architecture that is computer controlled, and a composition that mimics the mineral composition of natural bone. The HA/β-TCP biphasic material used as a control material in this study was prepared using conventional foaming based methods. No signs of inflammatory reactions were observed post-operatively for both materials. After 4 months signs of fusion at the osteotomy site and good integration of the implanted wedges were observed, showing good mechanical resistance. Concerning the final correction attained, the left knee revealed a satisfactory valgus of 10°, but the right one only had a final value of 6°. The clinical evaluation using International Knee Score (IKS) showed good outcome in all parameters with complete range of motion in both knees and climbing stairs without crutches with only slight pain. © 2007 Springer Science+Business Media, LLC.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-007-3171-xPubMed ID: 17569003Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratório de Biomateriais, Instituto de Engenharia Biomédica (INEB), Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; Bone Substitutes; Calcium Phosphates; Ceratite, 124097-42-3; HydroxyapatitesTradenames: BonelikeReferences: Gaasbeek, R.D.A., Welsing, R.T.C., Verdonschot, N., Rijnberg, W.J., Van Loon, C.J.M., Van Kampen, A., (2005) Knee Surg. Sports Traumatol. Arthrosc., 13, p. 689. , 8;Scott, W.N., Clarke, H.D., (2004) Orthopedics, 27, p. 975. , 9; Virolainen, P., Aro, H.T., (2004) Arch. Orthop. Trauma Surg., 124, p. 258. , 4; Wright, J.M., Crockett, H.C., Slawski, D.P., Madsen, M.W., Windsor, R.E., (2005) J. Am. Acad. Orthop. Surg., 13, p. 279. , 4; Fujisawa, Y., Masura, K., Shiomi, S., (1979) Clin. Orthop. North Am., 10, p. 585; Odenbridge, S., Egund, N., Lindstrand, A., Lohmander, L.S., Willen, H., (1992) Clin Orthop., 277, p. 210; Koshino, T., Wada, S., Ara, Y., Saito, T., (2003) Knee, 10, p. 229; Hernigou, P., (2002) Knee, 9, p. 15. , 1; Hoell, S., Suttmoeller, J., Stoll, V., Fuchs, S., Gosheger, G., (2005) Arch. Orthop. Trauma Surg., 125, p. 638. , 9; Betz, R.R., (2002) Orthopedics, 25, p. 561. , 5; Legeros, R.Z., (2002) Clin. Orthop. Relat. Res., 395, p. 81; Steffen, T., Stoll, T., Arvinte, T., Schenk, R.K., (2001) Eur. Spine J., 10, p. 132; Chu, T.M.G., Orton, D.G., Hollister, S.J., Feinberg, S.E., Halloran, J.W., (2002) Biomaterials, 23, p. 1283. , 5; Hutmacher, D.W., Sittinger, M., Risbud, M.V., (2004) Trends Biotechnol., 22, p. 354. , 7; Jones, J.R., Ehrenfried, L.M., Hench, L.L., (2006) Biomaterials, 27, p. 964. , 7; Gauthier, O., Bouler, J.M., Aguado, E., Pilet, P., Daculsi, G., (1998) Biomaterials, 19, p. 133. , 1-3; LU, J.X., Flautre, B., Anselme, K., Hardouin, P., Gallur, A., Descamps, M., Thierry, B., (1999) J. Mater. Sci. Mater. Med., 10, p. 111. , 2; Martina, M., Subramanyam, G., Weaver, J.C., Hutmacher, D.W., Morse, D.E., Valiyaveettil, S., (2005) Biomaterials, 26, p. 5609. , 28; Moroni, L., De Wijn, J.R., Van Blitterswijk, C.A., (2006) Biomaterials, 27, p. 974. , 7; Duarte, F., Santos, J.D., Afonso, A., (2004) Adv. Mater. Forum, 455-456, p. 370; Lobato, J.V., Hussain, N.S., Botelho, C.M., Mauricio, A.C., Lobato, J.M., Lopes, M.A., Afonso, A., Santos, J.D., (2006) Thin Solid Films, 515, p. 279. , 1; Gutierres, M., Hussain, N.S., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Santos, J.D., (2005) Bioceramics, 17, p. 1041; Lobato, J.V., Hussain, N.S., Botelho, C.M., Rodrigues, J.M., Luís, A.L., Maurício, A.C., Lopes, M.A., Santos, J.D., (2005) Key Eng. Mater., 284-286, p. 877; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463; Leong, K.F., Cheah, C.M., Chua, C.K., (2003) Biomaterials, 24, p. 2363. , 13; Hutmacher, D.W., (2001) J. Biomater. Sci. Polym. Ed., 12, p. 107. , 1; Santos, J., Hastings, G., Knowles, J., Sintered hydroxyapatite compositions and method for the preparation thereof (1999), Worldwide Application (PCT), Patent No. 1 189 851Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244. , 2; Lopes, M.A., Knowles, J.C., Santos, J.D., (2000) Biomaterials, 21, p. 1905. , 18; Schwartz, C., Liss, P., Jacquemaire, B., Lecestre, P., Frayssinet, P., (1999) J. Mater. Sci. Mater. Med., 10, p. 821. , 12; Van Hemert, W.L.W., Willems, K., Anderson, P.G., Van Heerwaarden, R.J., Wymenga, A.B., (2004) Knee, 11, p. 451. , 6; Gaasbeek, R.D.A., Toonen, H.G., Van Heerwaarden, R.J., Buma, P., (2005) Biomaterials, 26, p. 6713. , 33; Hernigou, P., Ma, W., (2001) Knee, 8, p. 103. , 2; Koshino, T., Murase, T., Saito, T., (2003) J. Bone Joint Surg. Am., 85, p. 78. , 1; Koshino, T., Murase, T., Takagi, T., Saito, T., (2001) Biomaterials, 22, p. 1579. , 12; Zhim, F., Laflamme, G.Y., Viens, H., Saidane, K., Yahia, L., (2005) Clin. Biomech., 20, p. 871. , 8; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 20, p. 2085. , 21; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 48, p. 734. , 5
Keywords: adult; article; Biological organs; Biomodeling; Bone; bone allograft; Bone graft; bone mineral; Bone Substitutes; calcium phosphate; Calcium phosphates; case report; climbing; clinical evaluation; Computer simulation; Grafts; human; Humans; hydroxyapatite; Hydroxyapatites; Imaging, Three-Dimensional; knee; knee pain; Macroporous structures; male; Mechanical properties; Middle Aged; Osteoarthritis; Osteoarthritis, Knee; Osteoblasts; osteotomy; pain assessment; porosity; Porous wedge shapes; priority journal; Prostheses and Implants; range of motion; structure analysis; tibia; tibia osteotomy; Tibial osteotomy; Valgus; valgus knee

Physicochemical degradation studies of calcium phosphate glass ceramic in the CaO-P 2O 5-MgO-TiO 2 system - Dias, A.G.; Gibson, I.R.; Santos, J.D.; Lopes, M.A. (Acta BiomaterialiaActa Biomater., 2007)
The aim of this work was to evaluate the in vitro degradation behaviour of a 45CaO-37P 2O 5-5MgO-13TiO 2 (mol.%) glass ceramic, under two different simulated physiological conditions: normal physiological pH 7.4, and pH 3.0, which was designed to simulate the acidic conditions produced by osteoclast cells. The in vitro testing was carried out at 37 °C for up to 42 days for the pH 7.4 solution and for up to 1 day for the pH 3.0 solution. The incorporation of TiO 2 into the glass structure leads to the precipitation of specific crystalline phases in the glass matrix, namely α- and β-Ca 2P 2O 7, TiP 2O 7 and CaTi 4(PO 4) 6. The degradation testing at pH 3.0 showed a higher weight loss compared with degradation testing at pH 7.4; the weight loss under the acidic condition after 1 day (24 h) was about 10 times higher than the weight loss after 42 days of immersion at pH 7.4. The ionic release profile of Ca 2+, PO 4 3 -, Mg 2+ and Ti 4+ showed a continuous increase in concentration over all immersion times for both testing solutions. After 1 day of immersion at pH 3.0, the concentration levels of Mg 2+, Ca 2+, PO 4 3 - were about six times higher than the levels achieved after 42 days of immersion at pH 7.4. The glass ceramic showed similar degradation to hydroxyapatite, and therefore has potential to be used in certain clinical applications where relatively slow resorption of the implant and replacement by bone is required, e.g. cranioplasty. © 2006 Acta Materialia Inc.
Cited By (since 1996): 5Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2006.09.009PubMed ID: 17150421Language of Original Document: EnglishCorrespondence Address: Lopes, M.A.; Instituto de Engenharia Biomédica (INEB), Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: malopes@fe.up.ptChemicals/CAS: calcium ion, 14127-61-8; hydroxyapatite, 1306-06-5, 51198-94-8; phosphate, 14066-19-4, 14265-44-2; titanium, 7440-32-6; Biocompatible Materials; Calcium Compounds; calcium phosphate, 10103-46-5; Calcium Phosphates; Ceramics; Glass ceramics, 85422-94-2; lime, 1305-78-8; Magnesium Oxide, 1309-48-4; Oxides; Phosphorus Compounds; phosphorus pentoxide, 1314-56-3; titanium dioxide, 13463-67-7; Titanium, 7440-32-6References: (2003) Bone graft substitutes, , Laurencin C.T. (Ed), ASTM International;(1993) Introduction to bioceramics, , Hench L.L., and Wilson J. (Eds), World Scientific, Singapore; Ratner, B.D., Bryant, S.J., Biomaterials: where we have been and where we are going (2004) Ann Rev Biomed Eng, 6, p. 41; Fuchs, J.R., Nasseri, B.A., Vacanti, J.P., Tissue engineering: a 21st century solution to surgical reconstruction (2001) Ann Thorac Surg, 72, p. 577; Nasseri, B.A., Ogawa, K., Vacanti, J.P., Tissue engineering: an evolving 21st-century science to provide biologic replacement for reconstruction and transplantation (2001) Surgery, 130, p. 781; Stock, U.A., Vacanti, J.P., Tissue engineering: current state and prospects (2001) Ann Rev Med, 52, p. 443; Burnie, J., Gilchrist, T., Controlled release glass (CRG) - a new biomaterials (1983) Ceramics in Surgery, p. 169. , Vicenzi P. (Ed), Elsevier, Amsterdam; Burnie, J., Gilchrist, T., Duff, S.R.I., Drake, C.F., Harding, N.G.L., Malcolm, A.J., Controlled release glasses (CRG) for biomedical uses (1981) Biomaterials, 2, p. 244; (2004) Biomaterials Science: An Introduction to Materials in Medicine, , Ratner B.D., Hoffmam A.S., Schoen F.J., and Lemons F.J. (Eds), Elsevier, Amsterdam; Vogel, J., Wange, P., Hartmann, P., Phosphate glasses and glass-ceramics for medical applications (1997) Glastech Ber-Glass, 70, p. 220; Dorozhkin, S.V., Epple, M., Biological and medical significance of calcium phosphates (2002) Angew Chem Int Edit, 41, p. 3130; Grambow, B., Geochemical approach to glass dissolution (1992) Corrosion of Glass, Ceramics and Ceramic Superconductors, , Clark D.E., and Zoitos B.K. (Eds), Noyes, Park Ridge, NJ; Legeros, R.Z., Biodegradation and bioresorption of calcium phosphate ceramics (1993) Clin Mater, 14, p. 65; Lettuec, J.C., Clément, D., Lesprit, E., Faber, J., The use of calcium phosphates, their biological properties (2000) Eur J Orthopaedic Surg Traumatol, 10, p. 223; McCracken, W.J., Corrosion of glass-ceramics (1992) Corrosion of Glass, Ceramics and Ceramic Superconductors, , Clark D.E., and Zoitos B.K. (Eds), Noyes, Park Ridge, NJ; Dias, A.G., Costa, M.A., Lopes, M.A., Santos, J.D., Fernandes, M.H., Biological activity of two glass ceramics in the meta- and pyrophosphate region: a comparative study (2004) Key Eng Mater, 254-256, p. 825; Dias, A.G., Lopes, M.A., Afonso, A.A., Tsuru, K., Hayakawa, S., Takashima, S., In vivo performance of biodegradable calcium phosphate glass ceramics using the rabbit model: histological and SEM observation (2006) J Biomater Appl, 20, p. 253; Dias, A.G., Lopes, M.A., Cabral, A.T.T., Santos, J.D., Fernandes, M.H., In vitro studies of calcium phosphate glass ceramics with different solubility with the use of human bone marrow cells (2005) J Biomed Mater Res A, 74 A, p. 347; Dias, A.G., Skakle, J.M.S., Gibson, I.R., Lopes, M.A., Santos, J.D., In situ thermal and structural characterization of bioactive calcium phosphate glass ceramics containing TiO 2 and MgO oxides: high temperature XRD studies (2005) J Non-Cryst Solids, 351, p. 810; Baron, R., Neff, L., Louvard, D., Courtoy, P.J., Cell-mediated extracellular acidification and bone-resorption - evidence for a low ph in resorbing lacunae and localization of a 100-kD lysosomal membrane-protein at the osteoclast ruffled border (1985) J Cell Biol, 101, p. 2210; Teitelbaum, S.L., Bone resorption by osteoclasts (2000) Science, 289, p. 1504; Dias, A.G., Tsuru, K., Hayakawa, T., Lopes, M.A., Santos, J.D., Osaka, A., Crystallisation studies of biodegradable CaO-P 2O 5 glass with MgO and TiO 2 for bone regeneration applications (2004) Glass Tech, 45, p. 78; Nyquist, R.A., (1997) Handbook of infrared and raman spectra of inorganic compounds and organics salts, , Academic Press, New York; Tadic, D., Epple, M., A thorough physicochemical characterisation of 14 calcium phosphate-based bone substitution materials in comparison to natural bone (2004) Biomaterials, 25, p. 987; Ploska, U., Berger, G., Solubility of compositions in the system CaTixZr 4 - x(PO 4) 6 with x = 0-4 (1997) Biomaterials, 18, p. 1671; Lin, F.H., Liao, C.J., Chen, K.S., Sun, J.S., Liu, H.C., Degradation behaviour of a new bioceramic: Ca 2P 2O 7 with addition of Na 4P 2O 7 · 10H 2O (1997) Biomaterials, 18, p. 915; Koerten, H.K., van der Meulen, J., Degradation of calcium phosphate ceramics (1999) J Biomed Mater Res, 44, p. 78; Athanasou, N.A., Cellular biology of bone-resorbing cells (1996) J Bone Joint Surg Am, 78, p. 1096; Aoki, H., (1991) Science and medical applications of hydroxyapatite, , Takayama Press, Tokyo; Aoki, H., (1994) Medical applications of hydroxypatite, , Ishiyaku EuroAmerica, Inc., Tokyo; Hennequin, M., Douillard, Y., Effects of citric-acid treatment on the Ca, P and Mg contents of human dental roots (1995) J Clin Periodontol, 22, p. 550; Hennequin, M., Pajot, J., Avignant, D., Effects of different pH values of citric-acid solutions on the calcium and phosphorus contents of human root dentin (1994) J Endod, 20, p. 551; Misra, D.N., Interaction of citric-acid with hydroxyapatite - formation of calcium citrate (1995) J Dent Res, 74, p. 72; Misra, D.N., Interaction of citric acid with hydroxyapatite: surface exchange of ions and precipitation of calcium citrate (1996) J Dent Res, 75, p. 1418; Ribeiro, C.C., Barbosa, M.A., Machado, A., Tudor, A., Davies, M.C., Modifications in the molecular structure of hydroxyapatite induced by titanium ions (1995) J Mater Sci Mater Med, 6, p. 829; Tanizawa, Y., Sawamura, K., Suzuki, T., Reaction characteristics of dental and synthetic apatites with Al 3+ and La 3+ ions in acidic solutions (1990) J Chem Soc Faraday T, 86, p. 4025; Tanizawa, Y., Sawamura, K., Suzuki, T., Reaction characteristics of dental and synthetic apatites with Fe 2+ and Fe 3+ ions (1990) J Chem Soc Faraday T, 86, p. 1071; Gross, U., Muller-Mai, C., Voigt, C., Mesgarian, M., Berger, G., Ploska, U., Tissue response in the femur of rabbits after implantation of a new calcium titanium phosphate composition (2001) Key Eng Mater, 192-195, p. 383; Kitsugi, T.l.T., Yamamuro, T., Nakamura, T., Oka, M., Transmission electron microscopy observations at the interface of bone and four types of calcium phosphate ceramics with different calcium/phosphorous molar ratios (1995) Biomaterials, 16, p. 1101; Sun, J.-S., Chang, W.H.-S., Chen, L.-T., Huang, Y.-C., Juang, L.-W., Lin, F.-H., The influence on gene-expression profiling of osteoblasts behavior following treatment with the ionic products of sintered β-dicalcium pyrophosphate dissolution (2004) Biomaterials, 25, p. 607; Chun, S., Na, S.W., Lee, J.H., Chung, J.P., Ryu, I.C., Kim, S.Y., Biodegradation study of potassium calcium metaphosphate in the SBF and Tris-buffer solution (2002) Key Eng Mater, 218-220, p. 149
Keywords: acidity; article; Biocompatible Materials; Biomaterials; Bone; Bone and Bones; bone prosthesis; Calcium Compounds; calcium ion; calcium phosphate ceramic; Calcium phosphates; ceramics; Chemical structure; concentration response; controlled study; cranioplasty; Crystallization; Degradation; glass; Hydrogen-Ion Concentration; hydroxyapatite; In vitro biodegradation; in vitro study; Magnesium Oxide; materials testing; Microscopy, Electron, Scanning; Models, Statistical; osteoclast; Oxides; pH; phosphate; Phosphorus Compounds; physical chemistry; priority journal; prosthesis material; simulation; Spectrum Analysis, Raman; structure analysis; temperature; Time Factors; Titanium; weight reduction

Upregulation of bone cell differentiation through immobilization within a synthetic extracellular matrix - Evangelista, M.B.; Hsiong, S.X.; Fernandes, R.; Sampaio, P.; Kong, H.-J.; Barrias, C.C.; Salema, R.; Barbosa, M.A.; Mooney, D.J.; Granja, P.L. (BiomaterialsBiomaterials, 2007)
There is a need for new therapeutic strategies to treat bone defects caused by trauma, disease or tissue loss. Injectable systems for cell transplantation have the advantage of allowing the use of minimally invasive surgical procedures, and thus for less discomfort to patients. In the present study, it is hypothesized that Arg-Gly-Asp (RGD)-coupled in a binary (low and high molecular weight) injectable alginate composition is able to influence bone cell differentiation in a three-dimensional (3D) structure. Viability, metabolic activity, cytoskeleton organization, ultrastructure and differentiation (alkaline phosphatase (ALP), von Kossa, alizarin red stainings and osteocalcin quantification) of immobilized cells were assessed. Cells within RGD-modified alginate microspheres were able to establish more interactions with the synthetic extracellular matrix as visualized by confocal laser scanning microscope and transmission electron microscopy imaging, and presented a much higher level of differentiation (more intense ALP and mineralization stainings and higher levels of osteocalcin secretion) when compared to cells immobilized within unmodified alginate microspheres. These findings demonstrate that peptides covalently coupled to alginate were efficient in influencing cell behavior within this 3D system, and may provide adequate preparation of osteoblasts for cell transplantation. © 2007 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 39Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2007.04.028PubMed ID: 17532040Language of Original Document: EnglishCorrespondence Address: Evangelista, M.B.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: mbe@ineb.up.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; alkaline phosphatase, 9001-78-9; arginylglycylaspartic acid, 99896-85-2; DNA, 9007-49-2; osteocalcin, 136461-80-8; Alginates; alginic acid, 9005-32-7; Alkaline Phosphatase, EC 3.1.3.1; arginyl-glycyl-aspartic acid, 99896-85-2; Glucuronic Acid, 576-37-4; Hexuronic Acids; Oligopeptides; Osteocalcin, 104982-03-8References: de Vos, P., de Haan, B., Wolters, G.H.J., VanSchilfgaarde, R., Factors influencing the adequacy of microencapsulation of rat pancreatic islets (1996) Transplantation, 62 (7), pp. 888-893;Brissova, M., Lacik, I., Powers, A.C., Anilkumar, A.V., Wang, T., Control and measurement of permeability for design of microcapsule cell delivery system (1998) J Biomed Mater Res, 39 (1), pp. 61-70; Strand, B.L., Gaserod, O., Kulseng, B., Espevik, T., Skjak-Braek, G., Alginate-polylysine-alginate microcapsules: effect of size reduction on capsule properties (2002) J Microencapsul, 19 (5), pp. 615-630; Chang, T.M.S., Artificial liver support based on artificial cells with emphasis on encapsulated hepatocytes (1992) Artif Organs, 16 (1), pp. 71-74; Uludag, H., Sefton, M.V., Microencapsulated human hepatoma (HepG2) cells-in-vitro growth and protein release (1993) J Biomed Mater Res, 27 (10), pp. 1213-1224; Canaple, L., Rehor, A., Hunkeler, D., Improving cell encapsulation through size control (2002) J Biomater Sci Polym Ed, 13 (7), pp. 783-796; Temenoff, J.S., Mikos, A.G., Injectable biodegradable materials for orthopedic tissue engineering (2000) Biomaterials, 21 (23), pp. 2405-2412; LeBaron, R.G., Athanasiou, K.A., Extracellular matrix cell adhesion peptides: functional applications in orthopedic materials (2000) Tissue Eng, 6 (2), pp. 85-103; Gumbiner, B.M., Cell adhesion: the molecular basis of tissue architecture and morphogenesis (1996) Cell, 84 (3), pp. 345-357; Majmudar, G., Bole, D., Goldstein, S.A., Bonadio, J., Bone cell-culture in a 3-dimensional polymer bead stabilizes the differentiated phenotype and provides evidence that osteoblastic cells synthesize type-III collagen and fibronectin (1991) J Bone Miner Res, 6 (8), pp. 869-881; Payne, R.G., Yaszemski, M.J., Yasko, A.W., Mikos, A.G., Development of an injectable, in situ crosslinkable, degradable polymeric carrier for osteogenic cell populations. Part 1. Encapsulation of marrow stromal osteoblasts in surface crosslinked gelatin microparticles (2002) Biomaterials, 23 (22), pp. 4359-4371; Lee, K.Y., Alsberg, E., Mooney, D.J., Degradable and injectable poly(aldehyde guluronate) hydrogels for bone tissue engineering (2001) J Biomed Mater Res, 56 (2), pp. 228-233; Alsberg, E., Anderson, K.W., Albeiruti, A., Franceschi, R.T., Mooney, D.J., Cell-interactive alginate hydrogels for bone tissue engineering (2001) J Dental Res, 80 (11), pp. 2025-2029; Burdick, J.A., Anseth, K.S., Photoencapsulation of osteoblasts in injectable RGD-modified PEG hydrogels for bone tissue engineering (2002) Biomaterials, 23 (22), pp. 4315-4323; Smidsrod, O., Skjak-Braek, G., Alginate as immobilization matrix for cells (1990) Trends Biotechnol, 8 (3), pp. 71-78; Boontheekul, T., Kong, H.J., Mooney, D.J., Controlling alginate gel degradation utilizing partial oxidation and bimodal molecular weight distribution (2005) Biomaterials, 26 (15), pp. 2455-2465; Kong, H.J., Alsberg, E., Kaigler, D., Lee, K.Y., Mooney, D.J., Controlling degradation of hydrogels via the size of cross-linked junctions (2004) Adv Mater, 16 (21), pp. 1917-1921; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20 (1), pp. 45-53; Bouhadir, K.H., Lee, K.Y., Alsberg, E., Damm, K.L., Anderson, K.W., Mooney, D.J., Degradation of partially oxidized alginate and its potential application for tissue engineering (2001) Biotechnol Prog, 17 (5), pp. 945-950; Kong, H.J., Smith, M.K., Mooney, D.J., Designing alginate hydrogels to maintain viability of immobilized cells (2003) Biomaterials, 24 (22), pp. 4023-4029; Bouhadir, K.H., Hausman, D.S., Mooney, D.J., Synthesis of cross-linked poly(aldehyde guluronate) hydrogels (1999) Polymer, 40 (12), pp. 3575-3584; Labarca, C., Paigen, K., Simple, rapid, and sensitive DNA assay procedure (1980) Anal Biochem, 102 (2), pp. 344-352; Caron, J.M., Kirschner, M.W., Autoregulation of tubulin synthesis (1986) Bioessays, 5 (5), pp. 211-216; Poole, C.A., Brookes, N.H., Clover, G.M., Keratocyte networks visualised in the living cornea using vital dyes (1993) J Cell Sci, 106, pp. 685-691; Li, R.H., Altreuter, D.H., Gentile, F.T., Transport characterization of hydrogel matrices for cell encapsulation (1996) Biotechnol Bioeng, 50 (4), pp. 365-373; Dulieu, C., Poncelet, D., Neufeld, R.J., Encapsulation and immobilization techniques (1999) Cell encapsulation technology and therapeutics, pp. 3-17. , Kühtreiber W.M., Lanza R.P., and Chick W.L. (Eds), Birkhäuser, Boston; Peirone, M., Ross, C.J.D., Hortelano, G., Brash, J.L., Chang, P.L., Encapsulation of various recombinant mammalian cell types in different alginate microcapsules (1998) J Biomed Mater Res, 42 (4), pp. 587-596; Kong, H.J., Kaigler, D., Kim, K., Mooney, D.J., Controlling rigidity and degradation of alginate hydrogels via molecular weight distribution (2004) Biomacromolecules, 5 (5), pp. 1720-1727; Boninsegna, S., Dal Toso, R., Dal Monte, R., Alginate microspheres loaded with animal cells and coated by a siliceous layer (2003) J Sol-Gel Sci Technol, 26 (1-3), pp. 1151-1157; Rokstad, A.M., Donati, I., Borgogna, M., Oberholzer, J., Strand, B.L., Espevik, T., Cell-compatible covalently reinforced beads obtained from a chemoenzymatically engineered alginate (2006) Biomaterials, 27 (27), pp. 4726-4737; Lu, M.Z., Lan, H.L., Wang, F.F., Chang, S.J., Wang, Y.J., Cell encapsulation with alginate and alpha-phenoxycinnamylidene-acetylated poly(allylamine) (2000) Biotechnol Bioeng, 70 (5), pp. 479-483; Stein, G.S., Lian, J.B., Molecular mechanisms mediating proliferation differentiation interrelationships during progressive development of the osteoblast phenotype (1993) Endocrine Rev, 14 (4), pp. 424-442; Siebers, M.C., ter Brugge, P.J., Walboomers, X.F., Jansen, J.A., Integrins as linker proteins between osteoblasts and bone replacing materials. A critical review (2005) Biomaterials, 26 (2), pp. 137-146; Hynes, R.O., Integrins: bidirectional, allosteric signaling machines (2002) Cell, 110 (6), pp. 673-687; Giancotti, F.G., Ruoslahti, E., Transduction-integrin signaling (1999) Science, 285 (5430), pp. 1028-1032; Payne, R.G., McGonigle, J.S., Yaszemski, M.J., Yasko, A.W., Mikos, A.G., Development of an injectable, in situ crosslinkable, degradable polymeric carrier for osteogenic cell populations. Part 2. Viability of encapsulated marrow stromal osteoblasts cultured on crosslinking poly(propylene fumarate) (2002) Biomaterials, 23 (22), pp. 4373-4380; Franceschi, R.T., Iyer, B.S., Relationship between collagen-synthesis and expression of the osteoblast phenotype in MC3T3-E1 cells (1992) J Bone Miner Res, 7 (2), pp. 235-246; Franceschi, R.T., The developmental control of osteoblast-specific gene expression: role of specific transcription factors and the extracellular matrix environment (1999) Crit Rev Oral Biol Med, 10 (1), pp. 40-57; Gerstenfeld, L.C., Chipman, S.D., Kelly, C.M., Hodgens, K.J., Lee, D.D., Landis, W.J., Collagen expression, ultrastructural assembly, and mineralization in cultures of chicken-embryo osteoblasts (1988) J Cell Biol, 106 (3), pp. 979-989; Dudley, H.R., Spiro, D., Fine structure of bone cells (1961) J Biophys Biochem Cytol, 11 (3), pp. 627-649; Holtrop, M.E., The ultrastructure of bone (1975) Ann Clin Lab Sci, 5 (4), pp. 264-271; Rhodin, J.A.G., (1963) An atlas of ultrastructure, , W. B. Saunders Company, Philadelphia; Trojani, C., Weiss, P., Michiels, J.F., Vinatier, C., Guicheux, J., Daculsi, G., Three-dimensional culture and differentiation of human osteogenic cells in an injectable hydroxypropylmethylcellulose hydrogel (2005) Biomaterials, 26 (27), pp. 5509-5517; Kneser, U., Voogd, A., Ohnolz, J., Buettner, O., Stangenberg, L., Zhang, Y.H., Fibrin gel-immobilized primary osteoblasts in calcium phosphate bone cement: in vivo evaluation with regard to application as injectable biological bone substitute (2005) Cells Tissues Organs, 179 (4), pp. 158-169; Bancroft, J.D., Gamble, M., (2002) Theory and practice of histological techniques. 5th ed, , Elsevier Science, Edinburgh
Keywords: 3T3 Cells; Alginate; Alginates; alginic acid; alkaline phosphatase; animal cell; Animals; arginylglycylaspartic acid; article; Bone; bone cell; Bone Regeneration; calvaria; cell adhesion; cell differentiation; Cell encapsulation; Cell immobilization; cell metabolism; cell proliferation; cell survival; cell ultrastructure; cell viability; confocal laser microscopy; controlled study; cytology; cytoskeleton; DNA; DNA content; ECM (extracellular matrix); enzyme activity; extracellular matrix; Glucuronic Acid; Hexuronic Acids; hydrogel; immobilized cell; metabolism; Mice; Microscopy, Confocal; Microscopy, Electron, Transmission; microsphere; Microspheres; nonhuman; Oligopeptides; osteoblast; Osteoblasts; osteocalcin; Patient treatment; priority journal; rat; RGD peptide; structure analysis; three dimensional imaging; Tissue engineering; transmission electron microscopy; Transplantation (surgical)

31P MAS-NMR studies of CaO-P 2O 5 glass ceramics - Dias, A.G.; Lopes, M.A.; Tsuru, K.; Hayakawa, S.; Santos, J.D.; Osaka', A. (Key Engineering MaterialsKey Eng Mat, 2006)
This work reports the structure of two glass ceramics prepared in the calcium phosphate system, MK5B and MT13B, using 31P MAS-NMR technique. The results obtained showed that the network of MK5B consisted mainly of Q 1 and Q 2 groups. Besides these two groups, MT13B material also present Q 3 units. The Q n groups detected in both glass ceramics seem to be correlated to the crystalline phases present in their microstructure.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Dias, A.G.; Instituto de Engenharia Biomédica (INEB), Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: agdias@fe.up.ptReferences: Jäger, C., Hartmann, P., Witter, R., Braun, M., (2000) J. Non-cryst. Solids, 263, p. 61;Hartmann, P., Vogel, J., Schnabel, B., (1994) J. Non-cryst. Solids, 176, p. 157; Dias, A.G., Lopes, M.A., Gibson, I.R., Santos, J.D., (2003) J. Non-cryst. Solids, 330, p. 81; Dias, A.G., Skakle, J.M.S., Gibson, I.R., Lopes, M.A., Santos, J.D., (2005) J. Non-cryst. Solids, 351, p. 810; Brow, R.K., (2000) J. Non-cryst. Solids, 263, p. 1; Hayakawa, S., Tsuru, S., Iida, H., Ohtsuki, C., Osaka, A., (1996) Phys. Chem. Glasses, 37, p. 188; Brown, R.K., Tallant, D.R., Warren, W.L., McIntyre, A., Day, D.E., (1997) Phys. Chem. Glasses, 38, p. 300; Kirkpatrick, R.J., Brown, R.K., (1995) Sol. Stat. Nucl. Mag. Resonance, 5, p. 9
Keywords: Biomaterials; calcium phosphate; Crystalline materials; Crystalline phases; Glass ceramics; Lime; MAS-NMR technique; Microstructure; NMR; Nuclear magnetic resonance spectroscopy

Absorption and emission properties of Ho 3+ doped lead-zinc-borate glasses - Sooraj Hussain, N.; Ali, N.; Dias, A.G.; Lopes, M.A.; Santos, J.D.; Buddhudu, S. (Thin Solid FilmsThin Solid Films, 2006)
This paper reports on the affect of lead content on the absorption and emission spectra of the Ho 3+ ion doped lead-zinc-borate glasses in the composition (mol%) of (20 - x)PbO-20ZnO-(59 + x)B 2O 3-1.0Ho 2O 3 where x = 0, 5,10,15 of PbO content with λ exc = 405 nm. The experimental absorption band energies have satisfactorily been correlated with the theoretical results with an r.m.s deviation of zero with the following correction factors obtained by a least square fit analysis: ΔE 1 = 348.495936 cm
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: THSFAdoi: 10.1016/j.tsf.2005.12.085Language of Original Document: EnglishCorrespondence Address: Sooraj Hussain, N.; DEMM, Faculty of Eng. University of Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: sooraj@fe.up.ptReferences: Song, J.H., Jong Heo, Park, S.H., (2003) J. Appl. Phys., 93, p. 9441;Chen, Q., Ferraris, M., Menke, Y., Milanese, D., Monchiero, E., (2003) J.Non-Cryst. Solids, 324, p. 1; Kassab, L.R.P., Courrol, L.C., Morais, A.S., Mendes, C.M.S.P., Tatumi, S.H., Wetter, N.U., Gomes, L., Salvador, V.L.R., (2002) J.Non-Cryst. Solids, 304, p. 233; Kityk, I.V., Wasylak, J., Kucharski, J., Dorosz, D., (2002) J .Non-Cryst. Solids, 297, p. 285; Souza Filho, A.G., Mendes Filho, J., Melo, F.E.A., Custodio, M.C.C., Lebullenger, R., Hernandes, A.C., (2000) .J. Phys. Chem. Solids, 61, p. 1535; Choi, Y.G., Jong Heo, (1997) J. Non-Cryst. Solids, 217, p. 199; Koepke, Cz., Wisniewski, K., Sikorski, L., Piatkowski, D., Kowalska, K., Naftaly, M., (2006) Opt. Mater., 28, p. 129; Szachowicz, M., Tascu, S., Joubert, M.-F., Moretti, P., Nikl, M., (2006) Opt. Mater., 28, p. 162; Kassab, L.R.P., de Oliveira Preto, A., Lozano, W., de Sá, F.X., Maciel, G.S., (2005) J. Non-Cryst. Solids, 351, p. 3468; Lavín, V., Lahoz, F., Martín, I.R., Rodríguez-Mendoza, U.R., Cáceres, J.M., (2005) Opt. Mater., 27, p. 1754; Karmakar, B., (2005) J. Solid State Chem., 178, p. 2663; Pisarski, W.A., Goryczka, T., Wodecka-Duś, B., Płońska, M., Pisarska, J., (2005) Mater. Sci. Eng., 122, p. 94; Speghini, A., Peruffo, M., Casarin, M., Ajo, D., Bettinelli, M., (2000) J. Alloys Comp., 300-301, p. 174; Fermi, F., Ingletto, G., Aschieri, C., Bettinelli, M., (1989) Inorg. Chim. Acta, 163, p. 123; Ingletto, Bettinelli, M., Di Sipio, L., Negrisolo, F., Aschieri, C., (1991) Inorg. Chim. Acta, 188, p. 201; Saisudha, M.B., Ramakrishna, J., (1996) Phys. Rev., B, 53, p. 6186; Zahara, A.-M., Zahra, C.Y., (1993) J. Non-Cryst. Solids, 155, p. 45; Motke, S.G., Yawale, S.P., Yawale, S.S., (2002) Bull. Mater. Sci., 25, p. 75; Peres, T., Litton, D.A., Capobianco, J.A., Garofalini, S.H., (1997) J. Non-Cryst. Solids, 221, p. 34; Reddy, M.R., Raju, S.B., Veeraiah, N., (2000) J. Phys. Chem. Solids, 61, p. 1567; Prasad, N.V.V., Annapurna, K., Sooraj Hussain, N., Buddhudu, S., (2003) Mater. Lett., 57, p. 2071; Sooraj Hussain, N., Prabhakara Reddy, Y., Buddhudu, S., (2001) Mater. Lett., 48, p. 303; Sooraj Hussain, N., Prabhakara Reddy, Y., Buddhudu, S., (2002) Spectrosc. Lett., 35 (2), p. 275; Sooraj Hussain, N., Prabhakara Reddy, Y., Rajamohan Reddy, K., Buddhudu, S., (2001) Phys. Chem. Glasses, 42 (6), p. 358; Sooraj Hussain, N., Annapurna, K., Prabhakara Reddy, Y., Buddhudu, S., (2002) J. Mater. Sci. Lett., 21, p. 397; Sooraj Hussain, N., Prabhakara Reddy, Y., Buddhudu, S., (2001) Mater. Res. Bull., 36, p. 1813; Sooraj Hussain, N., Prabhakara Reddy, Y., Buddhudu, S., (2002) Mater. Lett., 52, p. 429; Lakshminarayana, G., Buddhudu, S., (2005) Spectrochim. Acta, A, 62, p. 364; Judd, B.R., (1962) Phys. Rev., 127, p. 750; Ofelt, G.S., (1962) J. Chem. Phys., 37, p. 511; Weber, M.J., Matsinger, B.H., Domlan, V.L., Surratt, G.T., (1972) J. Chem. Phys., 57, p. 562; Rukmini, E., Jayasankar, C.K., (1995) Opt. Mater., 4, p. 529; Auzel, F., (1987) Spectroscopy of Solid State Lase-Type Materials, , Di Bartolo B. (Ed), Plenum, New York; Guery, C., Adam, J.L., Lucas, J., (1987) J. Lumin., 42, p. 266; Shelby, J.E., Ruller, J., (1987) Phys. Chem. Glasses, 28, p. 262; Wong, E.Y., (1961) J. Chem. Phys., 35, p. 544; Wong, E.Y., (1963) J. Chem. Phys., 38, p. 976; Hufner, S., (1978) Optical Spectra of Transparent Rare-Earth Compounds, , Academic Press, New York; Jorgensen, C.K., (1962) Orbitals in Atoms and Molecules, , Academic Press, London; Sinha, S.P., (1966) Complexes of Rare-Earths, , Pergamon Press, Oxford; Rao, T.V.R., Reddy, R.R., Nazeer Ahammed, Y., Parandamaiah, M., Sooraj Hussain, N., Buddhudu, S., Purandar, K., (2000) Infrared Phys. Technol., 41, p. 247; Weber, M.J., Ziegler, D.C., Angell, C.A., (1982) J. Appl. Phys., 53, p. 4344; Rai, S.B., (2002) Spectrochim. Acta, A, 58, p. 1559; Rakov, N., Maciel, G.S., de Araujo, C.B., Messaddeq, Y., (2002) J. Appl. Phys., 91, p. 1272; Villacampa, B., Orera, V.M., Merino, R.I., Cases, R., Alonso, P.J., Alcalá, R., (1991) Mater. Res. Bull., 26, p. 741; Weber, M.J., Matsinger, B.H., Donlan, V.L., Surratt, G.T., (1972) J. Chem. Phys., 57, p. 562; Quagliano, J.R., Richardson, F.S., Reid, M.F., (1992) J. Alloys Compd., 180, p. 131; McDugall, J., Hollis, D.B., Payne, M.J.P., (1994) Phys. Chem. Glasses, 35, p. 258; Cases, R., Chamarro, M.A., (1991) J. Solid State Chem., 90, p. 313
Keywords: Band energies; Doping (additives); Energy gap; glass; Glasses; Holmium; Holmium glasses; Light absorption; Luminescence; Luminescences; Luminescent transitions; Optical properties; Stimulated emission

Adsorption of albumin on prosthetic materials: Implication for tribological behavior - Serro, A.P.; Gispert, M.P.; Martins, M.C.L.; Brogueira, P.; Colaço, R.; Saramago, B. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
The orthopedic prosthesis used to substitute damaged natural joints are lubricated by a pseudosynovial fluid that contains biological macromolecules with potential boundary lubrication properties. Proteins are some of those macromolecules whose role in the lubrication process is not yet completely understood. In a previous work, we investigated the influence of the presence of albumin, the major synovial protein, upon the tribological behavior of three of the most used pairs of artificial joint materials: ultra high molecular weight polyethylene (UHMWPE) against counterfaces of alumina, CoCrMo alloy, and 316L stainless steel. Albumin was found to cause a significant decrease in the friction coefficient when the counterfaces were metallic because transfer of UHMWPE was avoided, but this effect was much weaker in the case of alumina. The objective of the present work was to look for an explanation for these differences in tribological behavior in terms of albumin adsorption. With this goal, studies on adsorption of bovine serum albumin (BSA) on the counterface materials, from a biological model fluid (Hanks' balanced salt solution), were carried out using radiolabeled albumin ( 125I-BSA), X-ray photoelectron spectroscopy, and atomic force microscopy. The conclusion from all techniques is that the driving force for albumin adsorption is higher on the metals than on alumina. These results confirm that the greater the amount of protein adsorbed on the counterface, the more efficient is the protection against the transfer of polymeric film to the counterface. © 2006 Wiley Periodicals, Inc.
Cited By (since 1996): 25Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30754PubMed ID: 16739106Language of Original Document: EnglishCorrespondence Address: Serro, A.P.; Centro de Química Estrutural, Instituto Superior Técnico, Av. Rovisco Pais, 1049-001 Lisboa, Portugal; email: anapaula.serro@ist.utl.ptChemicals/CAS: aluminum oxide, 1302-74-5, 1318-23-6, 1344-28-1, 14762-49-3; iodine 125, 14158-31-7, 22822-81-7; molybdenum, 7439-98-7; protein, 67254-75-5; stainless steel, 12597-68-1; Albumins; Biocompatible MaterialsTradenames: CHIRULEN, Poly Hi Solidur, GermanyManufacturers: Maret, Switzerland; MediMet, Germany; Poly Hi Solidur, GermanyReferences: Widmer, M.R., Heuberger, M., Vörös, J., Spencer, N.D., Influence of polymer surface chemistry on frictional properties under protein-lubrication conditions: Implications for hip-implant design (2001) Tribol Lett, 10, pp. 111-116;Saikko, V., Effect of lubricant protein concentration on the wear of ultrahigh molecular weight polyethylene sliding against a CoCr counterface (2003) Trans ASME, 125, pp. 638-642; Sawae, Y., Murakami, T., Chen, J., Effect of synovia constituents on friction and wear of ultra-high molecular weight polyethylene sliding against prosthetic joint materials (1998) Wear, 216, pp. 213-219; Kumar, P., Oka, M., Ikeuchi, K., Shimizu, K., Yamamuro, T., Okumura, H., Kotoura, Y., Low wear rate of UHMWPE against zirconia ceramic (Y-PSZ) in comparison to alumina ceramic and SUS 316L alloy (1991) J Biomed Mater Res, 25, pp. 813-828; Kitano, T., Ateshian, G.A., Mow, V.C., Kadoya, Y., Yamano, Y., Constituents and pH changes in protein rich hyaluronan solution affect the biotribological properties of artificial cartilage (2001) J Biomech, 34, pp. 1031-1037; Gispert, M.P., Serro, A.P., Colaço, R., Saramago, B., Friction and wear mechanisms in hip prosthesis: Comparison of joint materials behaviour in several lubricants (2006) Wear, 260, pp. 149-158; Van Enckevort, H.J., Dass, D.V., Langdon, A.G., The adsorption of bovine serum albumin at the stainless-steel/aqueous solution interface (1984) J Colloid Interface Sci, 98, pp. 138-143; Fukuzaki, S., Urano, H., Nagata, K., Adsorption of protein onto stainless-steel surfaces (1995) J Ferment Bioeng, 80, pp. 6-11; Rubio, C., Costa, D., Bellon-Fontaine, M.N., Relkin, P., Pradier, C.M., Marcus, P., Characterization of bovine serum albumin adsorption on chromium and AISI 304 stainless steel, consequences for the Pseudomonas fragi K1 adhesion (2002) Colloid Surf B Biointerface, 24, pp. 193-205; Sakiyama, T., Tomura, J., Imamura, K., Nakanishi, K., Adsorption characteristics of bovine serum albumin and its peptide fragments on a stainless steel surface (2004) Colloid Surf B Biointerface, 33, pp. 77-84; Fukuzaki, S., Urano, H., Yamaguchi, T., Effect of modification of alumina surfaces by ozone on adsorption behaviour of bovine serum albumin at alumina-water interfaces (1997) J Ferment Bioeng, 84, pp. 407-413; Urano, H., Fukuzaki, S., Conformation of adsorbed bovine serum albumin governing its desorption behavior at alumina-water interfaces (2000) J Ferm Bioeng, 90, pp. 105-110; Williams, R.L., Williams, D.F., Albumin adsorption on metal surfaces (1998) Biomaterials, 9, pp. 206-212; Haynes, C.A., Norde, W., Globular proteins at solid/liquid interfaces (1994) Colloid Surf B Biointerface, 2, pp. 517-566; Owens, D.K., Wendt, R.C., Estimation of the surface free energy of polymers (1969) J Appl Polym Sci, 13, pp. 1741-1747; Michalski, M.C., Hardy, J., Saramago, B., On the surface tension of PVC/EVA polymer blends: Comparison of different calculation methods (1998) J Colloid Interface Sci, 208, pp. 319-328; Cheng, P., Li, D., Boruvka, L., Rotenberg, Y., Neumann, A.W., Automation zof axisymmetric drop shape analysis for measurements of interfacial tensions and contact angles (1990) Colloid Surf, 43, pp. 151-197; Cheng, P., Neumann, A.W., Computational evaluation of Axisymmetric Drop Shape Analysis - Profile (ADSA-P) (1992) Colloid Surf, 62, pp. 297-306; (1990) Practical Surface Analysis, Vol. 1: Auger and X-Ray Photoelectron Spectroscopy, 1. , Briggs D, Seah MP, editors. Cichester: Wiley; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., Interactions between calcium, phosphate, and albumin on the surface of titanium (2001) J Biomed Mater Res, 55, pp. 45-53; (1993) Iodine-125, a Guide to Radioiodination Techniques, p. 64. , Little Chalfont, Buckinghamshire, UK: Amersham Life Science; Feng, L., Andrade, J.D., Protein adsorption on low temperature isotropic carbon. III. Isotherms, competitivity, desorption and exchange of albumin and fibrinogen (1994) Biomaterials, 15, pp. 323-333; Paynter, R.W., Ratner, B.D., Horbett, T.A., Thomas, H.R., XPS studies on the organization of adsorbed protein films on fluoropolymers (1984) J Colloid Interface Sci, 101, pp. 233-245; Paynter, R.W., Ratner, B.D., The study of interfacial proteins and biomolecules by X-ray photoelectron spectroscopy (1985) Surface and Interfacial Aspects of Biomedical Polymers, Vol. 2: Protein Adsorption, 2, pp. 189-216. , Andrade JD, editor. New York: Plenum; Seah, M.P., Dench, W.A., Quantitative electron spectroscopy of surfaces: A standard data base for electron inelastic mean free paths in solids (1979) Surf Interface Anal, 1, pp. 2-11; Tanuma, S., Powell, C.J., Penn, D.R., Calculations of electron inelastic mean free paths. II. Data for 27 elements over the 50-2000 eV range (1991) Surf Interface Anal, 17, pp. 911-926; Carter, D.C., He, X.M., Munson, S.H., Twigg, P.D., Gernet, K.M., Broom, M.B., Miller, T.Y., Three-dimensional structure of human serum albumin (1989) Science, 244, pp. 1195-1198; Pradier, C.M., Costa, D., Rubio, C., Compère, C., Marcus, P., Role of salts on BSA adsorption on stainless steel in aqueous solutions. I. FT-IRRAS and XPS characterization (2002) Surf Interface Anal, 34, pp. 50-54; Lori, J.A., Hanawa, T., Adsorption characteristics of albumin on gold and titanium metals in Hanks' solution using EQCM (2004) Spectroscopy, 18, pp. 545-552; Sousa, S.R., Moradas-Ferreira, P., Saramago, B., Melo, L.V., Barbosa, M.A., Human serum albumin adsorption on TiO 2 from single protein solutions and from plasma (2004) Langmuir, 20, pp. 9745-9754; Uyen, H.M.W., Schakenraad, J.M., Sjollema, J., Noordmans, J., Jongebloed, W.L., Stokroos, I., Busscher, H.J., Amount and different surface structure of albumin adsorbed to solid substrata with different wettabilities in a parallel plate flow cell (1990) J Biomed Mater Res, 24, pp. 1599-1614; Young, B.R., Pitt, W.G., Cooper, S.L., Protein adsorption on polymeric biomaterials. II. Adsoption kinetics (1988) J Colloid Interface Sci, 125, pp. 246-260; Dulm, P.V., Norde, W., The adsorption of human plasma albumin on solid surfaces, with special attention to the kinetic aspects (1983) J Colloid Interface Sci, 91, pp. 248-255; Malmsten, M., Formation of adsorbed protein layers (1998) J Colloid Interface Sci, 207, pp. 186-199; Smith, I.O., Baumann, M.J., McCabe, L.R., Electrostatic interactions as a predictor for osteoblast attachment to biomaterials (2004) J Biomed Mater Res A, 70, pp. 436-441
Keywords: Adsorption; Albumin; Albumin adsorption; Albumins; Alumina; aluminum oxide; article; Atomic force microscopy; balanced salt solution; Biocompatible Materials; Body fluids; bovine serum albumin; chromium derivative; Cobalt alloy; Cobalt alloys; cobalt derivative; force; Friction; iodine 125; isotope labeling; joint fracture; Joints (anatomy); lubrication; macromolecule; metal; molecular weight; molybdenum; orthopedic prosthesis; orthopedics; Polyethylenes; polymer; Prostheses and Implants; prosthesis material; Prosthetics; protein; Proteins; Pseudosynovial fluid; Stainless steel; Thermodynamics; Tribology; ultra high molecular weight polyethylene; Ultra high molecular weight polyethylene (UHMWPE); X ray photoelectron spectroscopy

Assessment of Bonelike® graft with a resorbable matrix using an animal model - Lobato, J.V.; Hussain, N.S.; Botelho, C.M.; Maurício, A.C.; Afonso, A.; Ali, N.; Santos, J.D. (Thin Solid FilmsThin Solid Films, 2006)
Synthetic bone grafts have been developed to provide an alternative to autografts and allografts. Bonelike® is a patented synthetic osteoconductive bone graft that mimics the mineral composition of natural bone. In the present preliminary animal studies a user-friendly version of synthetic bone graft Bonelike® have been developed by using a resorbable matrix, Floseal®, as a vehicle and raloxifene hydrochloride as a therapeutic molecule, that is known to decrease osteoclast activity and therefore enhanced bone formation. From histological and scanning electron microscopy evaluations, the use of Bonelike® associated with Floseal® and raloxifene hydrochloride showed that new bone was rapidly apposed on implanted granules and also that the presence of the matrix and therapeutic molecule does not alter the proven highly osteoconductivity properties of Bonelike®. Therefore, this association may be one step-forward for the clinical applications of Bonelike® scaffolds since it is much more easy-to-handle when compared to granular materials. © 2006 Elsevier B.V. All rights reserved.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: THSFAdoi: 10.1016/j.tsf.2005.12.153Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Hench, L.L., Wilson, J., (1993) An Introduction to Bioceramics, Singapore, , Scientific W. (Ed);Hench, L.L., (1998) Biomaterials, 19, p. 1419; Giannoudis, P.V., Dinopoulos, H., Tsiridis, E., (2005) Injury, 36 S, pp. S20; Murugan, R., Ramakrishma, S., (2005) Compos. Sci. Technol., 65, p. 2385; Ewers, R., Simons, B., (1992) Biomaterials-Hard tissue repair and replacement, pp. 67-80. , Elsiever, The Netherlands; Ilan, D.I., Ladd, A.L., (2002) Oper. Tech. Plast. Reconstr. Surg., 9, p. 151; Mary, E.A.R., Raymond, A.Y., (1998) Dent. Clin. North Am., 42, p. 491; Keating, J., McQueen, M., (2001) J. Bone Jt. Surg., 83 B, p. 3; Summers, B.M., Eisenstein, S.M., (2001) J. Bone Jt. Surg., 71 B, p. 677; Younger, E.M., Chapman, M.W., (1989) J. Orthop. Trauma, 3, p. 192; LeGeros, R.Z., (2002) Clin. Orthop. Res., 395, p. 81; Daculsi, G., (1998) Biomaterials, 19, p. 1473; Bohner, M., van Lenthe, G.H., Grunenfelder, S., Hirsiger, W., Evison, R., Muller, R., (2005) Biomaterials, 26, p. 6099; LeGeros, R.Z., (1981) Prog. Cryst. Growth Charact., 1-2, p. 1; LeGeros, R.Z., (1993) Dense Hydroxyapatite, An Introduction to Bioceramics, , World Scientific, Singapore; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 20, p. 2085; Lopes, M.A., Silva, R.F., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 21, p. 749; Lopes, M.A., Knowles, J.C., Santos, J.D., (2000) Biomaterials, 21, p. 1905; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Oslen, I., (1998) J. Biomed. Mater. Res., 41, p. 649; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., (2000) Biomaterials, 21, p. 1165; Mathiasen, R.A., Cruz, R.M., (2004) Otolaryngol. Head Neck Surg., 131, p. 601; User, H.M., Robert, B.N., (2003) Urology, 62, p. 342; Kheirabadi, B.S., Field-Redley, A., Pearson, R., MacPhee, M., Drohan, W., Tuthill, D., (2002) J. Surg. Res., 106, p. 99; Gill, I.S., Ramani, A.P., Spaliviero, M., Xu, M., Finelli, A., Kaouk, J.H., Desai, M.M., (2005) Urology, 65, p. 463; Weaver, F.A., Hood, D.B., Zatina, M., Messina, L., Badduke, B., (2002) Ann. Vasc. Surg., 16, p. 286; Ettinger, B., Genant, H.K., Cann, C.E., (1985) Ann. Intern. Med., 102, p. 319; Manolagas, S., Kousteni, S., Jilka, R., (2002) Recent Prog. Horm. Res., 57, p. 385; Trontelj, J., Vovk, T., Bogataj, M., Mrhar, A., (2005) Pharmacol. Res., 52, p. 334; Bryant, H., Glasebrook, A.L., Yang, N.N., Sato, M., (1999) J. Steroid Biochem. Mol. Biol., 69, p. 37; Bjarnason, N.H., Haarbo, J., Byrjalsen, I., Alexandersen, P., Kauffman, R.F., Christiansen, C., (2001) Atherosclerosis, 154, p. 97; Somjen, D., Yoles, I., (2003) J. Steroid Biochem. Mol. Biol., 86, p. 93; Buelke-Sam, J., Bryant, H.U., Francis, P.C., (1998) Reprod. Toxicol., 12, p. 217; Black, L.J., Sato, M., Rowley, E.R., Magee, D.E., Bekele, A., Williams, D.C., Cullinan, G.J., Bryant, H.U., (1994) J. Clin. Invest., 93, p. 63; Delmas, P.D., Bjarnason, N.H., Mitlak, B.H., Ravoux, A.C., Shah, A.S., Huster, W.J., Draper, M., Christiansen, C., (1997) N. Engl. J. Med., 337, p. 1641; Lobato, J.V., Sooraj Hussain, N., Botelho, C.M., Rodrigues, J.M., Luis, A.L., Mauricio, A.C., Lopes, M.A., Santos, J.D., (2005) Key Eng. Mater., 284-286, p. 877; Gutierres, M., Sooraj Hussain, N., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Santos, J.D., (2005) Key Eng. Mater., 284-286, p. 1041; Costa, M.A., Gutierres, M., Almeida, L., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2004) Key Eng. Mater., 254-256, p. 821; Duarte, F.M., Santos, J.D., Afonso, A., (2004) Mat. Sci. Forum, 455-456, p. 370; Ross, M.H., Romrell, L.J., Kaye, G.I., (1995) Histology a Text and Atlas, New York
Keywords: animal model; Bone; Bonelike®; FloSeal®; Grafting (chemical); Histological analysis; Mathematical models; Raloxifene hydrochloride; Scanning electron microscopy

The class imbalance problem in TLC image classification - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2006)
The paper presents the methodology developed to solve the class imbalanced problem that occurs in the classification of Thin-Layer Chromatography (TLC) images. The proposed methodology is based on resampling, and consists in the undersampling of the majority class (normal class), while the minority classes, which contain Lysosomal Storage Disorders (LSD) samples, are oversampled with the generation of synthetic samples. For image classification two approaches are presented, one based on a hierarchical classifier and another uses a multiclassifier system, where both classifiers are trained and tested using balanced data sets. The results demonstrate a better performance of the multiclassifier system using the balanced sets. © Springer-Verlag Berlin Heidelberg 2006.
Conference code: 68310Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Sousa, A.V.; Instituto Superior de Engenharia do Porto, Rua Dr. Antonio Bernardino de A. 431, 4200-072 Porto, Portugal; email: ats@isep.ipp.ptReferences: Kubat, M., Holte, R., Matwin, S., Learning when negative examples abound (1997) European Conference on Machine Learning, pp. 146-153;Lazarević, A., Srivastava, J., Kumar, V., Data mining for analysis of rare events: A case study in security, financial and medical applications (2004) PAKDD-2004; Skurichina, M., Raudys, S., Duin, R.P.W., K-nearest neighbors directed noise injection in multilayer perceptron training (2000) IEEE Transactions on Neural Networks, 11 (2); Chawla, N.V., Japkowicz, N., Kolcz, A., Editorial: Special issue on learning from imbalanced data sets (2004) Sigkdd Explorations, 6 (1), pp. 1-6; Japkowicz, N., Class imbalances: Are we focusing on the right issue? Workshop on Learning from Imbalanced Datasets II, p. 6. , (2003) ICML, Washington DC; Chawla, N.V., Lazarević, A., Hall, L.O., Bowyer, K.W., SMOTEBoost: Improving the prediction of minority class in boosting (2003) 7th European Conference on Principles and Practice of Knowledge Discovery in Databases (PKDD), pp. 107-119; Domingos, P., MetaCost: A general method for making classifiers cost-sensitive (1999) Conference on Knowledge Discovery in Data Proceedings of the Fifth ACM SIGKDD International Conference on Knowledge Discovery and Data Mining, pp. 155-164; Fan, W., Stolfo, S., Zhang, J., Chan, P., Adacost: Misclassication cost-sensitive boosting (1999) Proceedings of Sixteenth International Conference on Machine Learning, pp. 983-990; Tax, D.M.J., One-class classification; Concept-learning in the absence of counterexamples (2001) ASCI Dissertation Series, 65, pp. 1-190. , PhD thesis Delft University of Technology; Ridder, D., Tax, D.M.J., Duin, R.P.W., An experimental comparison of one-class classification methods (1998) Proc ASCI'98, 4th Annual Conf of the Advanced School for Computing and Imaging, pp. 213-218. , (Lommel, Belgium, June 9-11), ASCI, Delft; Lazarevic, A., Ertoz, L., Ozgur, A., Srivastava, J., Kumar, V., A comparative study of anomaly detection schemes in network intrusion detection (2003) Proceedings of Third SIAM Conference on Data Mining, , San Francisco; Weiss, G.M., Mining with rarity: A unifying framework (2004) Sigkdd Explorations, 6 (1), pp. 7-19; Lewis, D.D., Gale, W.A., A sequential algorithm for training text classifiers (1994) Proceedings of International ACM Conference on Research and Development in Information Retrieval, pp. 3-12; Visa, S., Ralescu, A., Learning imbalanced and overlapping classes using fuzzy sets (2003) Workshop on Learning from Imbalanced Datasets II, , ICML, Washington DC; Sousa, A.V., Aguiar, R., Mendonça, A.M., Campilho, A., Automatic lane and band detection in images of thin layer chromatography (2004) LNCS, 3212. , Springer; Sousa, A.V., Mendonça, A.M., Campilho, A., Aguiar, R., Miranda, C.S., Feature extraction for classification of thin-layer chromatography images (2005) LNCS, 3656. , Springer; Japkowicz, N., Learning from imbalanced data sets: A comparison of various strategies (2000) Proceedings of Learning from Imbalanced Data, pp. 10-15; Kubat, M., Holte, R., Matwin, S., Machine learning for the detection of oil spills in satellite radar images (1998) Machine Learning, 30, pp. 195-215; Ha, T., Bunke, H., Off-Line, handwritten numeral recognition by perturbation method (1997) Pattern Analysis and Machine Intelligence, 19 (5), pp. 535-539; Lee, S., Noisy replication in skewed binary classification (2000) Computational Statistics & Data Analysis; Heijden, F., Robert, P.W.D., Ridder, D., Tax, D.M.J., (2004) Classification, Parameter Estimation and State Estimation, , Wiley; Demant, C., Streicher-Abel, B., Waszkewitz, P., (1999) Industrial Image Processing, , Springer-Verlag; Chawla, N.V., Bowyer, K., Hall, L., Kegelmeyer, W., SMOTE: Synthetic minority over-sampling technique (2002) Jounal of Artificial Intelligence Research, 16, pp. 321-357
Keywords: Chromatographic analysis; Class imbalanced problem; Classification (of information); Hierarchical systems; Lysosomal Storage Disorders (LSD); Medical imaging; Multiclassifier system; Problem solving; Thin-Layer Chromatography (TLC) images

Differentiation of mononuclear precursors into osteoclasts on the surface of Si-substituted hydroxyapatite - Botelho, C.M.; Brooks, R.A.; Spence, G.; McFarlane, I.; Lopes, M.A.; Best, S.M.; Santos, J.D.; Rushton, N.; Bonfield, W. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
In healthy bone, resorption and synthesis are in perfect coordination. In previous studies we demonstrated that the incorporation of silicon into the hydroxyapatite (HA) lattice enhances the proliferation and differentiation of human osteoblasts. Therefore, the aim of this study was to demonstrate the effect of silicon-substituted HA (0.8 and 1.5 wt % Si-HA) on the differentiation of mononuclear cells into osteoclasts, using two different starting cultures, peripheral blood mononuclear cells (PBMC) and monocytes expressing the CD14 antigen (CD14 +). Through this study, it was possible to demonstrate that Si-HA allows the differentiation of mononuclear cells into mature osteoclasts, independent of the starting culture, PBMC or CD14 +. Most of the cells on the surface of the materials expressed osteoclastic markers: actin rings, several nuclei, positivity for tartrate-resistant acid phosphatase (TRAP), and vitronectin receptor. In the presence of osteoclasts, a higher release of calcium and phosphate into the medium from the 1.5 wt % Si-HA substrate was detected when compared to the HA substrate; therefore, these results indicate higher osteoclastic resorptive activity on the 1.5 wt % Si-HA surface. Si-HA can be resorbed by cellular mechanisms and have a stimulatory effect on osteoclasts, although the underlying mechanism is still poorly understood. © 2006 Wiley Periodicals, Inc.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30726PubMed ID: 16739170Language of Original Document: EnglishCorrespondence Address: Brooks, R.A.; Orthopaedic Research Unit, Box 180, Addenbrooke's Hospital, Hills Road, Cambridge CB2 2QQ, United Kingdom; email: rb10003@cam.ac.ukChemicals/CAS: calcium, 7440-70-2; hydroxyapatite, 1306-06-5, 51198-94-8; phosphate, 14066-19-4, 14265-44-2; silicon, 7440-21-3; Antigens, CD14; Durapatite, 1306-06-5; Silicon, 7440-21-3References: Schilling, A., Linhart, W., Filke, S., Gebauer, M., Schinke, T., Rueger, J., Amling, M., Resorbability of bone substitute biomaterials by human osteoclasts (2004) Biomaterials, 25, pp. 3963-3972;Miller, P., Baram, D., Bilezkian, J., Greenspan, S., Lindsay, R., Riggs, B., Watts, N., Practical clinical application of biochemical markers of bone turnover: Consensus of an expert panel (1999) J Clin Densitom, 2, pp. 323-342; Flanagan, A., Massey, H., Wilson, C., Vellodi, A., Horton, M.A., Steward, C., Macrophage colony-stimulating factor and receptor activator NF-κ B ligand fail to rescue osteoclast-poor human malignant infantile osteopetrosis in vitro (2002) Bone, 30, pp. 85-90; Boyle, W., Simonet, W., Lacey, D.L., Osteoclast differentiation and activation (2003) Nature, 423, pp. 337-342; Susa, M., Luong-Nguyen, N.H., Cappellen, D., Zamurovic, N., Gamse, R., Human primary osteoclasts in vitro generation and applications as a pharmacological and clinical assay (2004) J Transl Med, 2, p. 6; Anderson, D., Maraskovsky, E., Bilingsley, W., Dougal, W., Tometsko, M., Roux, E., Teepe, M., Gilbert, L., A homologue of the TNF receptor and its ligand enhance T-cell growth and dendritic-cell function (1997) Nature, 390, pp. 175-179; Matsuzaki, K., Udagawa, N., Takahashi, N., Yamaguchi, K., Yasuda, H., Shima, N., Morinaga, T., Suda, T., Osteoclast differentiation factor (ODF) induces osteoclast-like cell formation in human peripheral blood mononuclear cell cultures (1998) Biochem Biophys Res Commun, 246, pp. 199-204; Quinn, J., Elliot, J., Gillespie, M., Martin, T., A combination of Osteoclast differentiation factor and macrophage-colony stimulating factor is sufficient for both human and mouse osteoclast formation in vitro (1998) Endocrinology, 139, pp. 4424-4427; Massey, H., Flanagan, A., Human osteoclasts derive from CD14-positive monocytes (1999) Br J Haematol, 106, pp. 167-170; Horton, M., The α vβ 3 integrin "vitronectin receptor" (1997) Int J Biochem Cell Biol, 29, pp. 721-725; Doi, Y., Shibutani, T., Moriwaki, Y., Kajimoto, T., Iwayama, Y., Sintered carbonate apatites as bioresorbable bone substitutes (1998) J Biomed Mater Res, 39, pp. 603-610; Langstaff, S., Sayer, M., Smith, T., Pugh, S., Resorbable bioceramics based on stabilized calcium phosphates. Part II: Evaluation of biological response (2001) Biomaterials, 22, pp. 135-150; Patel, N., Best, S.M., Gibson, I.R., Hing, K.A., Damien, E., Revell, P.A., A comparative study on the in vivo behaviour of hydroxyapatite and silicon-substituted hydroxyapatite granules (2002) J Mater Sci Mater Med, 13, pp. 1199-1206; Botelho, C.M., Brooks, R.A., Lopes, M.A., Santos, J.D., Best, S.M., Rushton, N., Bonfield, W., Biological and physical-chemical characterization of phase pure hydroxyapatite and silicon-substituted hydroxyapatite by different microscopy techniques (2004) Key Eng Mater, 254-256, pp. 845-849; Gibson, I.R., Hung, J., Best, S.M., Bonfield, W., Enhanced in vitro cell activity and surface apatite layer formation on novel silicon-substituted hydroxyapatites (1999) Bioceramics, 12, pp. 191-194. , Ohgushi H, Hastings GW, Yoshikawa T, editors. Nara, Japan: World Scientific Publishing; Jha, L.J., Best, S.M., Santos, J.D., Gibson, I.R., Bonfield, W., Silicon-substituted apatites and process for the preparation thereof. Worldwide Pat PCT/GB97/02325, 1999Gibson, I., Best, S.M., Bonfield, W., Chemical characterization of silicon-substituted hydroxyapatite (1999) J Biomed Mater Res, 44 B, pp. 422-428; Botelho, C.M., Lopes, M.A., Gibson, I.R., Best, S.M., Santos, J.D., Structural analysis of Si-substituted hydroxyapatite: Zeta potential and X-ray photoelectron spectroscopy (XPS) (2002) J Mater Sci: Mater Med, 13, pp. 1123-1127; Winchester, R.J., Ross, G., Methods for enumerating lymphocyte populations (1976) Manual of Clinical Immunology, pp. 64-76. , Rose NR, Friedman H, editors. Washington, DC: American Society for Microbiology; Burstone, M.S., Histochemical demonstration of acid phosphatases with naphthol AS-phosphate (1958) J Natl Cancer Inst, 21, pp. 423-539; Monchau, F., Lefevre, A., Descamps, M., Belquin-Myrdyez, A., Laffargue, P., Hildebrand, H.F., In vitro studies of human and rat osteoclast activity on hydroxyapatite, β-tricalcium phosphate, calcium carbonate (2002) Biomol Eng, 19, pp. 143-152; Chambers, T.J., The regulation of osteoclastic development and function (1988) Ciba Foundation Symposium, 136, pp. 92-107; Lakkakorpi, P., Tuukkanen, J., Hentunen, J., Jarvelin, K., Vaananen, K., Organization of osteoclast microfilaments during the attachment to bone surface in vitro (1989) J Bone Miner Res, 4, pp. 817-825; Nesbitt, S., Horton, M.A., Trafficking of matrix collagens through bone-resorbing osteoclasts (1997) Science, 276, pp. 266-269; Salo, J., Lehenkari, P., Removal of osteoclast bone resorption products by transcytosis (1997) Science, 276, pp. 270-273; Vaananen, K., Horton, M.A., The osteoclast clear zone is a specialized cell extracellular matrix adhesion structure (1995) J Cell Sci, 108, pp. 2729-2732; Kong, Y.Y., Feige, U., Sarosi, I., Bolon, B., Tafuri, A., Morony, S., Cappareli, C., Boyle, W.J., OPGL is a key regulator of osteoclastogenesis, lymphocyte development and lymph-node organogenesis (1999) Nature, 402, pp. 304-309; Wittrant, Y., Thepleyre, S., Couillaud, S., Dunstan, C., Heymann, D., Rédini, F., Relevance of an in vitro osteoclastogenesis system to study receptor activator of NF-κ B ligand and osteoprotegerin biological activities (2004) Exp Cell Res, 93, pp. 292-301; Heymann, D., gp130 cytokine family and bone cells (2000) Cytokine, 12, pp. 1455-1468; Heymann, D., Gouin, F., Passuti, N., Daculsi, G., Cytokines, growth factors and osteoclasts (1998) Cytokine, 10, pp. 155-168; Burgess, T., Qian, Y., Kaufman, S., Ring, B., Van, G., Capparelli, C., The ligand for osteoprotegerin (OPGL) directly activates mature osteoclasts (1999) J Cell Biol, 145, pp. 527-538; Teitelbaum, S., Bone resorption by osteoclasts (2000) Science, 289, pp. 1504-1508; Udagawa, N., Takahashi, N., Jimi, E., Matsuzaki, K., Tsurukai, T., Itoh, K., Nakagawa, N., Goto, M., Osteoblasts/stromal cells stimulate osteoclast activation through expression of osteoclast differentiation factor/RANKL but not macrophage colony-stimulating factor (1999) Bone, 25, pp. 517-523; Zhang, Y.M., Cai, Y.R., Monchau, F., Lefevre, A., Zhao, Y.M., Hildebrand, H.F., Biodegradation of synthetic bioglass with different crystallinity in vitro (2004) Seventh World Biomaterials Congress, p. 1904. , Sydney; Gomi, K., Lowenberg, B., Shapiro, G., Davies, J.E., Resorption of sintered synthetic hydroxyapatite by osteoclasts in vitro (1993) Biomaterials, 2, pp. 91-96; De Bruijin, J.D., Bovel, Y.P., Davies, J.E., Van Blitterswijik, C.A., Osteoclastic resorption of calcium phosphate is potentiated in postosteogenic culture conditions (1994) J Biomed Mater Res, 28, pp. 105-112; Botelho, C.M., Brooks, R.A., Kawai, T., Ogata, S., Ohtsuki, C., Best, S.M., Lopes, M.A., Bonfield, W., In vitro analysis of protein adhesion to phase pure hydroxyapatite and silicon-substituted hydroxyapatite (2005) Key Eng Mat, 284-286, pp. 461-464
Keywords: acid phosphatase tartrate resistant isoenzyme; actin; Antigens, CD14; article; Biomarkers; Calcium; CD14 antigen; cell differentiation; Cells; controlled study; Differentiation; Durapatite; human; human cell; hydroxyapatite; Microscopy, Fluorescence; monocyte; Monocytes; Monocytes CD14 positive; Osteoblasts; osteoclast; Osteoclasts; osteolysis; peripheral blood mononuclear cell; Peripheral blood mononuclear cells; phosphate; Silicon; Silicon-substituted hydroxyapatite; Sorption; Substitution reactions; Substrates; surface property; Synthesis (chemical); vitronectin receptor

Effect of surface treatments on anodic oxide film growth and electrochemical properties of tantalum used for biomedical applications - Silva, R.A.; Silva, I.P.; Rondot, B. (Journal of Biomaterials ApplicationsJ. Biomater. Appl., 2006)
Self-expandable nitinol (nickel-titanium) alloys and 316L stainless steel are the most commonly used materials in the production of coronary stents. However, tantalum (Ta) has already been used to make stents for endovascular surgery and may constitute an alternative to other materials because of its better electrochemical performance, namely its higher corrosion resistance, as well as its radio-opacity. The characterization of wet polished, chemically polished, wet polished anodized, and chemically polished anodized Ta electrodes has been performed in a 0.15 M NaCl solution (simulated body fluid) using U corr=f(t) measurements, anodic polarizations, capacity measurements, anodic oxidations, and atomic force microscopy (AFM) imaging. Anodic polarization curves have shown that the abnormal current density peak with a maximum value around 1.65 V (critical applied potential, U c) disappeared for the anodized electrodes indicating a probable relationship between the surface states and the film growth. These results are confirmed by capacity measurements. The behavior of wet polished and chemically polished electrodes during anodic oxidations seemingly indicated that for these particular treatments the film growth is different. The AFM images and roughness measurements have shown that chemical polishing produced smoother electrodes, a fact probably related to the differences in film growth. © 2006 Sage Publications.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: JBAPEdoi: 10.1177/0885328206056378Language of Original Document: EnglishCorrespondence Address: Silva, R.A.; Instituto Superior de Engenharia do Porto, ISEP-CIEA, Rua Dr. A.B. de Almeida, 431, 4200-072 Porto, Portugal; email: ras@isep.ipp.ptChemicals/CAS: oxide, 16833-27-5; tantalum, 7440-25-7; Biocompatible Materials; Membranes, Artificial; Oxides; Tantalum, 7440-25-7References: Goy, J.J., Eeckhout, E., Stauffer, J.C., Vogt, P., Kappenberger, L., Emergency Endoluminal Stenting for Abrupt Vessel Closure following Coronary Angioplasty: A Randomised Comparison of the Wiktor and Palmaz-Schatz Stents (1995) Catheter. Cardiov. Diag., 34 (2), pp. 128-132;Hamasaki, N., Nosaka, H., Kimura, T., Nakagawa, Y., Yokoi, H., Nobuyioshi, M., Initial Experience with the Cordis Stent: Analysis of Serial Angiographic Follow-up (1995) Catheter. Cardiov. Diag., 42 (2), pp. 166-172; Hamm, C.W., Beythien, C., Sievert, H., Langer, A., Multicenter Evaluation of the Strecker Tantalum Stent for Acute Coronary Occlusion after Angioplasty (1995) Amer. Heart J., 129 (3), pp. 423-429; Strecker, E.-P.K., Boos, I.B.L., Göttman, D.V.S., Haase, W., Popliteal Artery Stenting Using Flexible Tantalum Stents (2001) Cardiovasc. Intervent. Radiol., 24 (3), pp. 168-175; Rieger, J., Hautmann, H., Linsenmaier, U., Weber, C., Treitl, M., Huber, R.M., Pfeifer, K.-J., Treatment of Benign and Malignant Tracheobronchial Obstruction with Metal Wire Stents: Experience with a Balloon-expandable and a Self Expandable Stent Type (2004) Cardiovasc. Intervent. Radiol., 27 (4), pp. 339-343; Bertrand, O.F., Sipehia, R., Mongrain, R., Rodes, J., Tardif, J.C., Bilodeau, L., Cote, G., Bourassa, M.G., Biocompatibility Aspect of New Stent Technology (1998) J. Am. Coll. Cardiol., 32 (3), pp. 562-571; Shih, C.-C., Lin, S.-J., Chung, K.-H., Chen, Y.-L., Su, Y.-Y., Increased Corrosion Resistance of Stent Materials by Converting Current Surface Film of Polycrystalline Oxide into Amorphous Oxide (2000) J. Biomed. Mater. Res., 52 (2), pp. 323-332; Thierry, B., Tabrizian, M., Trepanier, C., Savadogo, O., Yahia, L.H., Effect of Surface Treatment and Sterilization Processes on the Corrosion Behavior of NiTi Shape Memory Alloy (2000) J. Biomed. Mater. Res., 51 (4), pp. 685-693; Macionczyc, F., Gerold, B., Thull, R., Repassivating Tantalum/Tantalum Oxide Surface Modification on Stainless Steel (2001) Surface and Coatings Technology, 142-144, pp. 1085-1087; Starovesky, D., Gotman, I., Corrosion of Titanium Nitride Coated Ni-Ti Shape Memory Surgical Implant (2001) Biomaterials, 22 (13), pp. 1853-1859; Chen, J.Y., Leng, Y.X., Tian, X.B., Wang, L.P., Huang, N., Chu, P.K., Yang, P., Antithrombogenic Investigation of Surface Energy and Optical Bandgap and Hemocompatibility Mechanism of Ti(Ta(+5))O 2 (2002) Biomaterials, 23 (12), pp. 2545-2552; Tan, L., Crone, W.C., Sridharan, K., Fretting Study of Surface Modified Ni-Ti Shape Memory Alloy (2002) J. Mater. Sci. Mater. Med., 13 (5), pp. 501-508; Cissé, O., Savadogo, O., Wu, M., Yahia, L.H., Effect of Surface Treatment of NiTi Alloy on its Corrosion Behavior in Hank's Solution (2002) J. Biomed. Mater. Res., 61 (3), pp. 339-345; Schabalovskaya, S., Rondelli, G., Anderegg, J., Simpson, B., Budko, S., Effect of Chemical Etching and Aging in Boiling Water on the Corrosion Resistance of Nitinol Wires with Black Oxide Resulting from Manufacturing Process (2003) J. Biomed. Mater. Res., 66 B (1), pp. 331-340; Shih, C.-C., Shih, C.-M., Su, Y.-Y., Lin, S.-J., Impact on the Thrombogenicity of Surface Oxide Properties of 316L Stainless Steel for Biomedical Applications (2003) J. Biomed. Mater. Res., 67 A, pp. 1320-1328; Cheng, Y., Cai, W., Li, H.T., Zheng, Y.F., Zhao, L.C., Surface Characteristics and Corrosion Resistance Properties of TiNi Shape Memory Alloy Coated with Tantalum (2004) Surface and Coatings Technology, 186 (3), pp. 346-352; Silva, R.A., Marques, M.A., Silveira, A., Walls, M., Rondot, B., Guidoin, R., (1998) Proceedings of the 14th European Conference on Biomaterials, pp. 37-37. , (eds) In: Dutch Society for Biomaterials, September, The Hague; Pippen, C.M.J.M., Plenk Jr., H., Ebel, M.F., Svagera, R., Verenisch, J., Characterization of Microblasted and Reactive Ion Etched Surfaces on the Commercially Pure Metals Niobium, Tantalum and Titanium (1997) J. Mater. Sci.: Mater. in Med., 8 (12), pp. 781-784; Park, J.B., (1994) Biomaterials Science and Engineering, pp. 217-217. , (ed.) Plenum Press, New York; Jonhson, P.F., Bernstein, J.J., Hunter, G., Dawson, W.W., Hench, L.L., An in vitro and in vivo Analysis of Anodised Tantalum Capacitive Electrodes: Corrosion Response, Physiology, and Histology (1997) J. Biomed. Mater. Res., 11 (5), pp. 637-656; Black, J., Biological Performance of Tantalum (1994) Clin. Mater., 16 (3), pp. 167-173; Stackpool, G.J., Kay, A.B., Morton, P., Harvey, E.J., Tanzer, M., Bone, J.D., (1995) Proceedings of Combined Orthopaedic Research Societies Meeting, Orthopaedic, pp. 45-45. , (eds) In: Research Society Rider Dickerson Inc., Chicago; Silva, R.A., Walls, M., Rondot, B., Da Cunha Belo, M., Guidoin, R., Electrochemical and Microstructural Studies of Tantalum and its Oxide Films for Biomedical Applications in Endovascular Surgery (2002) J. Mater. Sci.: Mater. Medicine, 13 (5), pp. 495-500; Lohrengel, M.M., Formation of Ionic Space Charge Layers in Oxide Films on Valve Metals (1994) Electrochim. Acta, 39 (8-9), pp. 1265-1271; Macagno, V.A., Schultze, J.W., The Growth and Properties of Thin Oxide Layers on Tantalum Electrodes (1984) J. Electroanal. Chem., 180 (1), pp. 157-170; Schultze, J.W., Macagno, V.A., Electron Transfer Reaction on Passive Tantalum Electrodes (1986) Electrochim. Acta, 31 (1), pp. 355-363; Kerrec, O., Devilliers, D., Groult, H., Chemla, M., Dielectric Properties of Anodic Oxide Films on Tantalum (1995) Electrochim. Acta, 40 (6), pp. 719-724; Lewerenz, H.J., Anodic Oxide Films on Silicon (1992) Electrochim. Acta, 37 (10), pp. 847-851; Young, L., (1961) Anodic Oxide Films, , Academic Press, London; Seah, M.P., Holbourn, M.W., Ortega, C., Davies, J.A., An Intercomparison of Tantalum Pentoxide Reference Studies (1988) Nuclear Instruments and Methods in Physics Research, B30 (2), pp. 128-139
Keywords: AFM; Anodic films; Anodic oxide film growth; Anodic polarization; article; artificial membrane; Atomic force microscopy; Biocompatible Materials; biomaterial; Biomedical applications; Biomedical engineering; Chemical polishing; chemistry; Coronary stents; Corrosion resistance; Crystallization; Current density; electric conductivity; Electrochemical properties; electrochemistry; electrode; Electrodes; materials testing; Membranes, Artificial; methodology; oxidation reduction reaction; Oxidation-Reduction; oxide; Oxides; Polarization; Surface Properties; surface property; Surface treatment; Tantalum; Tantalum electrodes

Error entropy in classification problems: A univariate data analysis - Silva, L.M.; Felgueiras, C.S.; Alexandre, L.A.; Marques de Sá, J. (Neural ComputationNeural Comp., 2006)
Entropy-based cost functions are enjoying a growing attractiveness in unsupervised and supervised classification tasks. Better performances in terms both of error rate and speed of convergence have been reported. In this letter, we study the principle of error entropy minimization (EEM) from a theoretical point of view. We use Shannon's entropy and study univariate data splitting in two-class problems. In this setting, the error variable is a discrete random variable, leading to a not too complicated mathematical analysis of the error entropy. We start by showing that for uniformly distributed data, there is equivalence between the EEM split and the optimal classifier. In a more general setting, we prove the necessary conditions for this equivalence and show the existence of class configurations where the optimal classifier corresponds to maximum error entropy. The presented theoretical results provide practical guidelines that are illustrated with a set of experiments with both real and simulated data sets, where the effectiveness of EEM is compared with the usual mean square error minimization. © 2006 Massachusetts Institute of Technology.
Cited By (since 1996): 7Export Date: 21 November 2012Source: Scopusdoi: 10.1162/neco.2006.18.9.2036PubMed ID: 16846386Language of Original Document: EnglishCorrespondence Address: Silva, L.M.; Institute de Engenharia Biomédica, Laboratório Sinal e Imagem Biomédica, 4200-465, Porto, Portugal; email: lmsilva@fe.up.ptReferences: Devroye, L., Gyorfi, L., Lugosi, G., (1996) A Probabilistic Theory of Pattern Recognition, , Berlin: Springer-Verlag;Erdogmus, D., Principe, J., Comparison of entropy and mean square error criteria in adaptive system training using higher order statistics (2000) Proceedings of the Intl. Conf., on ICA and Signal Separation, pp. 75-80. , Helsinki, Finland; Erdogmus, D., Principe, J.C., An error-entropy minimization algorithm for supervised training of nonlinear adaptive systems (2002) IEEE Transactions on Signal Processing, 50 (7), pp. 1780-1786; Kapur, J., (1993) Maximum-entropy Models in Science and Engineering (Rev. Ed), , New York: Wiley; Kullback, S., (1959) Statistics and Information Theory, , New York: Wiley; Linsker, R., Self-organization in a perceptual network (1988) IEEE Computer, 21, pp. 105-117; Marques De Sa, J., (2001) Pattern Recognition: Concepts, Methods and Applications, , Berlin: Springer-Verlag; Newman, D., Hettich, S., Blake, C., Merz, C., (1998) UCI Repository of Machine Learning Databases, , http://www.ics.uci.edu/~mlearn/MLRepository.html, Irvine: University of California, Irvine, Department of Information and Computer Sciences; Parzen, E., On the estimation of a probability density function and the mode (1962) Annals of Mathematical Statistics, 33, pp. 1065-1076; Press, W., Teukolsky, S., Vetterling, W., Flannery, B., (1992) Numerical Recipes in C: The Art of Scientific Computing, , Cambridge: Cambridge University Press; Principe, J.C., Xu, D., Fisher, J., Information theoretic learning (2000) Unsupervised Adaptive Filtering, Vol. 1: Blind Source Separation, 1, pp. 265-319. , S. Haykin (Ed.), New York: Wiley; Santos, J., Alexandre, L., Marques De Sá, J., The error entropy minimization algorithm for neural network classification (2004) Int. Conf. on Recent Advances in Soft Computing, , Nottingham, U.K.: Nottingham Trent University; Santos, J., Marques De Sa, J., Alexandre, L., Sereno, F., Optimization of the error entropy minimization algorithm for neural network classification (2004) Intelligent Engineering Systems Through Artificial Neural Networks, 14, pp. 81-86. , C. Dagli, A. Buczak, D. Enke, M. Embrechts, & O. Ersoy (Eds.), New York: American Society of Mechanical Engineers; Shannon, C.E., A mathematical theory of communication (1948) Bell System Technical Journal, 27, pp. 379-423; Silva, L., Marques De Sa, J., Alexandre, L., Neural network classification using Shannon's entropy (2005) European Symposium on Artificial Neural Networks, , Bruges, Belgium: d-side publications; Silverman, B., (1986) Density Estimation for Statistics and Data Analysis, , London: Chapman & Hall; Stoller, D., Univariate two-population distribution free discrimination (1954) Journal of the American Statistical Association, 49, pp. 770-777
Keywords: article; Classification; entropy; methodology; Models, Theoretical; normal distribution; theoretical model

Functionalization of chitosan membranes through phosphorylation: Atomic force microscopy, wettability, and cytotoxicity studies - Amaral, I.F.; Granja, P.L.; Melo, L.V.; Saramago, B.; Barbosa, M.A. (Journal of Applied Polymer ScienceJ. Appl. Polym. Sci., 2006)
Grafting negatively charged groups such as phosphates is a well-known strategy for inducing the deposition of apatite-like layers under simulated physiological conditions. In this investigation, chitosan was phosphorylated in an attempt to enhance its osteoconduction. Chitosan membranes were phosphorylated at 30°C with the H 3PO 4/ Et 3PO 4/P 2O 5/butanol reaction system for periods up to 48 h. This method is an alternative to the phosphoric acid/ urea/dimethylformamide phosphorylation method, which involves the use of much higher temperatures. In this study, the effects of the phosphorylation reaction time on the surface morphology and surface free energy of phosphorylated membranes were investigated with atomic force microscopy and static-contact-angle measurements, respectively. In addition, the modified membranes were evaluated with respect to their cytotoxiciry toward bone cells through the incubation of human osteoblastic cells with extracts of the materials for two different periods: 24 and 120 h. The results revealed a reduction of the average surface roughness at the nanometer scale with increasing phosphorylation reaction time. Wettability studies showed an increase in the polar component of the surface free energy with increasing reaction time as a result of the increase in the phosphate surface concentration. Cytotoxicity studies revealed no cytotoxic effect of phosphorylated membranes on osteoblastic cells, regardless of the incubation period. © 2006 Wiley Periodicals, Inc.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: JAPNAdoi: 10.1002/app.23737Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; Laboratório de Biomateriais, Instituto de Engenharia Biomédica, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptReferences: Tomihata, K., Ikada, Y., (1997) Biomaterials, 18, p. 567;VandeVord, P.J., Matthew, H.W.T., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., (2002) J Biomed Mater Res, 59, p. 585; Khor, E.C., (2001) Fulfilling a Biomaterials Promise, , Elsevier: Oxford; Peluso, G., Petillo, O., Ranieri, M., Santin, M., Ambrosio, L., Calabro, D., Avallone, B., Balsamo, G., (1994) Biomaterials, 15, p. 1215; Muzzarelli, R.A.A., (1997) CeUul Mol Life Sci, 53, p. 131; Ishihara, M., Nakanishi, K., Ono, K., Sato, M., Kikuchi, M., Saito, Y., Yura, H., Kurita, A., (2002) Biomaterials, 23, p. 833; Muzzarelli, R.A.A., Zucchini, C., Ilari, P., Pugnaloni, A., Belmonte, M.M., Biagini, G., Castaldini, C., (1993) Biomaterials, 14, p. 925; Muzzarelli, R.A.A., Mattiolibelmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Fini, M., Biagini, G., (1994) Biomaterials, 15, p. 1075; Madihally, S.V., Matthew, H.W.T., (1999) Biomaterials, 20, p. 1133; Zhao, F., Yin, Y.J., Lu, W.W., Leong, J.C., Zhang, W.J., Zhang, J.Y., Zhang, M.F., Yao, K.D., (2002) Biomaterials, 23, p. 3227; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., (2000) J Biomed Mater Res, 51, p. 586; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., (2005) J Biomed Mater Res Part A, 75, p. 387; Muzzarelli, R.A.A., Muzzarelli, C., (2002) Chitosan in Pharmacy and Chemistry, p. 233. , Muzzarelli, R. A. A.; Muzzarelli, C., Eds.; Atec Edizioni: Grottammare, Italy; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., (2002) J Controlled Release, 78, p. 187; Ho, M.H., Wang, D.M., Hsieh, H.J., Liu, H.C., Hsien, T.Y., Lai, J.Y., Hou, L.T., (2005) Biomaterials, 26, p. 3197; Amaral, I.F., Cordeiro, A., Sampaio, P., Barbosa, M.A., J Biomat Sci: Polym, , accepted; Chatelet, C., Damour, O., Domard, A., (2001) Biomaterials, 22, p. 261; Hidaka, Y., Ito, M., Mori, K., Yagasaki, H., Kafrawy, A.H., (1999) J Biomed Mater Res, 46, p. 418; Mucalo, M.R., Yokogawa, Y., Suzuki, T., Kawamoto, Y., Nagata, F., Nishizawa, K., (1995) J Mater Sci: Mater Med, 6, p. 658; Tanahashi, M., Matsuda, T., (1997) J Biomed Mater Res, 34, p. 305; Yokogawa, Y., Rayes, J.P., Mucalo, M.R., Toriyama, M., Kawamoto, Y., Suzuki, T., Nishizawa, K., Kamayama, T., (1997) J Mater Sci: Mater Med, 8, p. 407; Granja, P.L., Barbosa, M.A., Pouysegu, L., De Jeso, B., Rouais, F., Baquey, C., (2001) J Mater Sci, 36, p. 2163; Amaral, I.F., Granja, P.L., Barbosa, M.A., (2005) J Biomater Sci Polym Ed, 16, p. 1575; Amaral, I.F., Granja, P.L., Barbosa, M.A., (2004) Key Eng Mater, 254, p. 577; Granja, P.L., Pouysegu, L., Petraud, M., De Jeso, B., Baquey, C., Barbosa, M.A., (2001) J Appl Polym Sci, 82, p. 3341; Touey, G.P., Kingsport, T., (1956), U.S. Pat. 2,759,924Fricain, J.C., Granja, P.L., Barbosa, M.A., De Jeso, B., Barthe, N., Baquey, C., (2002) Biomaterials, 23, p. 971; Sakaguchi, T., Horikoshi, T., Nakajima, A., (1981) Agric Biol Chem, 45, p. 2191; Sakairi, N., Shirai, A., Miyazaki, S., Tashiro, H., Tsuji, Y., Kawahara, H., Yoshida, T., Tokura, S., (1998) Kobunshi Ronbunshu, 55, p. 212; Lee, Y.M., Shin, E.M., (1991) J Membr Sci, 64, p. 145; Varma, H.K., Yokogawa, Y., Espinosa, F.F., Kawamoto, Y., Nishizawa, K., Nagata, F., Kameyama, T., (1999) Biomaterials, 20, p. 879; Yokogawa, Y., Nishizawa, K., Nagata, F., Kamayama, T., (1999) Bioceramics, p. 129. , Ohgushi, H.; Hastings, G. W.; Yoshikawa, T., Eds.; World Scientific: Singapore; Anselme, K., (2000) Biomaterials, 21, p. 667; Northup, S.J., Cammack, J., (1999) Handbook of Biomaterials Evaluation: Scientific, Technical, and Clinical Testing of Implant Materials, p. 325. , Recum, A. F., Ed.; Taylor & Francis: Philadelphia, PA; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., (2001) Polymer, 42, p. 3569; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., (1996) Carbohydr Polym, 29, p. 63; Grundke, K., Bogumil, T., Werner, C., Janke, A., Poschel, K., Jacobasch, H.J., (1996) Colloids Surf A, 116, p. 79; Kerkeb, M.L., Gonzalezcaballero, F., Chibowski, E., (1993) J Colloid Interface Sci, 159, p. 439; Andrade, J.D., Smith, L.M., Gregonis, D.E., (1985) Surface and Interfacial Aspects of Biomedical Polymers, p. 249. , Andrade, J. D., Ed.; Plenum: New York; Owens, D.K., Wendt, R.C., (1969) J Appl Polym Sci, 13, p. 1741; Berridge, M.V., Tan, A.S., McCoy, K.D., Wang, R., (1996) Biochemica, 4, p. 14; Mosmann, T., (1983) J Immunol Methods, 65, p. 55; Huang, R.Y.M., Moon, G.Y., Pal, R., (2001) J Membr Sci, 184, p. 1; Domke, J., Dannohl, S., Parak, W.J., Muller, O., Aicher, W.K., Radmacher, M., (2000) Colloids Surf B, 19, p. 367; MacDonald, D.E., Markovic, B., Allen, M., Somasundaran, P., Boskey, A.L., (1998) J Biomed Mater Res, 41, p. 120; Roberts, G.A.F., (1992) Chitin Chemistry, p. 350. , Macmillan: London; Andrade, J.D., (1992) Clin Mater, 11, p. 19; Wu, S., (1982) Polymer Interface and Adhesion, , Marcel Dekker: New York; Granja, P.L., Pouysegu, L., Deffieux, D., Daude, G., De Jeso, B., Labrugere, C., Baquey, C., Barbosa, M.A., (2001) J Appl Polym Sci, 82, p. 3354; Ratner, B.D., Caster, D.G., (1997) Surface Analysis - The Principal Techniques, p. 43. , Vickerman, J. C., Ed.; Wiley: Chichester, England; Barnes, A., Corkhill, P.H., Tighe, B.J., (1988) Polymer, 29, p. 2191; Domard, A., (1997) Advances in Chitin Science, p. 410. , Domard, A.; Roberts, G.; Vårum, K., Eds.; Jacques André: Lyon, France; Denuziere, A., Ferrier, D., Damour, O., Domard, A., (1998) Biomaterials, 19, p. 1275; Wang, X.H., Ma, J.B., Feng, Q.L., Cui, F.Z., (2002) Biomaterials, 23, p. 4591; Wang, X.H., Ma, J.B., Wang, Y.N., He, B.L., (2002) Biomaterials, 23, p. 4167; Hamano, T., Chiba, D., Nakatsuka, K., Nagahata, M., Teramoto, A., Kondo, Y., Hachimori, A., Abe, K., (2002) Polym Adv Technol, 13, p. 46
Keywords: Atomic force microscopy; Atomic force microscopy (AFM); Biocompatibility; Biological applications; Biological applications of polymers; Biomaterials; Chitin; chitosan; Chitosan membranes; grafting; Grafting (chemical); Osteoblastic cells; Phosphorylation; Polymeric membranes; polysaccharide; Polysaccharides; surface property; toxicity; Urea

Histological and scanning electron microscopy analyses of bone/implant interface using the novel Bonelike® synthetic bone graft - Gutierres, M.; Hussain, N.S.; Lopes, M.A.; Alfonso, A.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Journal of Orthopaedic ResearchJ. Orthop. Res., 2006)
Synthetic bone grafts provide an alternative to autografts and allografts. Bonelike® is a patented synthetic bone graft that mimics the mineral composition of bone. The aim of the present work was to assess the biological behavior of Bonelike® graft in humans, before using the material in orthopedic applications of bone regeneration, for example, in opening wedge high tibial osteotomies for medial knee osteoarthritis. Bonelike® granules were implanted in cortical bone of 11 patients undergoing osteotomies, and new bone formation, osteoconductive properties, and resorption characteristics of the granules were analyzed. The granules ranged from 500 to 1000 μm and were implanted in the lateral aspect of the tibia. The patients' mean age was 59 years (range 48 to 70 years); there were eight women and three men, all suffering from medial compartment osteoarthritis of the knee. At surgery, a 1 × 1 × 1-cm cortical defect was created 3 cm distal to the entry point of the screws, in line with the long axis of tibia. The implanted Bonelike® graft sample was extracted for analysis during removal of the metallic prosthesis after implantation times of 6, 9, and 12 months. Radiological follow-up, scanning electron microscopy, histological analysis, and histomorphometric measurements were conducted on the retrieved samples to assess bone regeneration in the defect area. Osteoconductive capacity was demonstrated by extensive mature bone formation around the implanted granules and high levels of percentage bone-to-graft contact (from 67-84%). Bonelike® acted as an excellent bioactive scaffold, allowing the migration, proliferation, and differentiation of bone cells on its surface, and therefore regeneration of the defects was achieved in a rapid, controlled manner. Our results suggest that Bonelike® graft is an excellent candidate for orthopedic applications where rapid new bone formation is a fundamental requirement. © 2006 Orthopaedic Research Society. Published by Wiley Periodicals, Inc.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JOREDdoi: 10.1002/jor.20117Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; DEMM, Faculty of Engg., University of Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Bone SubstitutesTradenames: Bonelike; JSM 630IF, JeolManufacturers: JeolReferences: Peter, P., Heinrich, R., Meinrad, P., (2003) Orthopaedic Issues in Osteoporosis, , YH An, editor. Boca Raton, FL: CRC Press;Hench, L.L., Wilson, J., (1999) An Introduction to Bioceramics, , Singapore: World Scientific Publishing Co. Pvt. Ltd; Corpe, R.S., Steflik, D.E., Whitehead, R.Y., Correlative experimental animal and human clinical retrieval evaluations (2000) Crit Rev Biomed Eng, 28, pp. 395-398; Kitsugi, T., Yamamuro, T., Nakamura, T., Four calcium phosphate ceramics as bone substitutes for non-weight bearing (1993) Biomaterials, 14, pp. 216-224; Koshino, T., Murase, T., Takagi, T., New bone formation around porous hydroxyapatite wedge implanted in opening wedge high tibial osteotomy in patients with osteoarthritis (2001) Biomaterials, 22, pp. 1579-1582; LeGeros, R.Z., (1991) Calcium Phosphates in Oral Biology and Medicine, pp. 4-45. , Meyers HM, editor. New York: Karger; Macdonald, D.E., Betts, F., Stranick, M., Physicochemical study of plasma-sprayed hydroxyapatite-coated implants in humans (2001) J Biomed Mater Res, 54, pp. 480-490; Oonishi, H., Yamamoto, M., Ishimaru, H., The effect of hydroxyapatite coating on bone growth into porous titanium alloy implants (1989) J Bone Surg Br, 71, pp. 213-216; Thomas, K.A., Hydroxyapatite coatings (1994) Orthopedics, 17, pp. 267-278; Doron, H., Amy, L.L., Bone graft substitutes (2003) Oper Tech Plastic Reconstruct Surg, 9, pp. 151-160; Write, S., The bone-graft market in Europe. Commentary extracted from a report entitled "Emerging technologies in orthopedics I.: Bone graft substitutes, bone growth stimulators and bone growth factors" (1999), pp. 591-595. , London: Datamonitor plcBotelho, C.M., Brooks, R.A., Best, S.M., Biological and physical-chemical characterization of phase pure HA and si-substituted hydroxyapatite by different microscopy techniques (2004) Key Eng Mater, 254, p. 845; Costa, M.A., Gutierres, M., Almeida, L., In vitro mineralisation of human bone marrow cells cultured on bonelike® (2004) Key Eng Mater, 254-256, pp. 821-824; Gutierres, M., Hussain, N.S., Afonso, A., Biological behaviour of bonelike® graft Implanted in the tibia of humans (2005) Key Eng Mater, 284-286, pp. 1041-1044; Lopes, M.A., Santos, J.D., Monteiro, F.J., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: Fracture toughness and hardness dependence on microstructural characteristics (1999) Biomaterials, 20, pp. 2085-2090; Lopes, M.A., Silva, R.F., Monteiro, F.J., Microstructural dependence of Young's and shear moduli of P 2O 5 glass reinforced hydroxyapatite for biomedical applications (2000) Biomaterials, 21, pp. 749-754; Lopes, M.A., Knowles, J.C., Santos, J.D., Structural insights of glass-reinforced hydroxyapatite composites by Rietveld refinement (2000) Biomaterials, 21, pp. 1905-1910; Santos, J.D., Knowles, J.C., Reis, R.L., Microstructural characterization of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Felson, D.T., Naimark, A., Anderson, J., The prevalence of knee osteoarthritis in the elderly: The Framingham Study (1987) Arthritis Rheum, 30, pp. 914-918; Guincamp, C., Pap, T., Schedel, J., Gene therapy in osteoarthritis (2000) Joint Bone Spine, 67, pp. 570-571; Marc, F., Serge, P., Mario, M.L.C., Assessment of the test-retest reliability and construct validity of a modified lequesne index in knee osteoarthritis (2003) Joint Bone Spine, 70, pp. 520-525; Pendleton, A., Arden, N., Dougados, M., EULAR recommendations for the management of knee osteoarthritis: Report of a task force of the Standing Committee for International Clinical Studies Including Therapeutic Trials (ESCISIT) (2000) Ann Rheum Dis, 59, pp. 936-944; Santos, J.D., Hastings, G.W., Knowles, J.C., Sintered hydroxyapatite compositions and method for the preparation thereof (1999) Eur. Pat. WO 0068164; Coventry, M.B., Osteotomy of the upper portion of the tibia for degenerative arthritis of the knee: A preliminary report (1965) J Bone Joint Surg Am, 47, p. 984; Hing, K.A., Assessment of porous hydroxyapatite for bone replacement (1996), (Ph D Thesis). London: University of LondonLopes, M.A., Knowles, J.C., Santos, J.D., Direct and indirect effects of P 2O 5-glass reinforced-hydroxyapatite composites and growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Knowles, J.C., Santos, J.D., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Ross, M.H., Romrell, L.J., Kaye, G.I., (1995) Histology - A Text and Atlas, , 3rd ed. Baltimore, MD: Williams & Wilkins; Lobato, J.V., Hussain, N.S., Botelho, C.M., Assessment of the potential of Bonelike® graft for bone regeneration by using an animal model (2005) Key Eng Mater, 284-286, pp. 877-880; Duarte, F., Lopes, M.A., Santos, J.D., Bonelike® composites for the regeneration of bone lesions (2004) Mater Sci Forum, 455-456, pp. 370-373; Laurencin, C.T., (2003) Bone Graft Substitutes, , West Conshohocken, PA: ASTM International
Keywords: adult; aged; article; Bone; Bone and Bones; bone cell; bone conduction; bone development; Bone graft; bone prosthesis; bone radiography; Bone Regeneration; bone screw; Bone Substitutes; bone transplantation; Bonelike®; cell differentiation; cell migration; cell proliferation; Clinical applications; clinical article; controlled study; Female; follow up; Histological analysis; histology; human; Humans; knee osteoarthritis; male; Microscopy, Electron, Scanning; Middle Aged; morphometrics; orthopedics; ossification; Osteoconduction; Osteogenesis; osteolysis; Pathology; priority journal; Prostheses and Implants; prostheses and orthoses; prosthesis material; Scanning electron microscopy; surgical technique; Synthetic bone graft; tibia osteotomy; ultrastructure

Human osteoblast response to silicon-substituted hydroxyapatite - Botelho, C.M.; Brooks, R.A.; Best, S.M.; Lopes, M.A.; Santos, J.D.; Rushton, N.; Bonfield, W. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
Human osteoblasts were cultured on hydroxyapatite (HA), 0.8 wt % silicon substituted hydroxyapatite (Si-HA) and 1.5 wt % Si-HA discs. The influence of these substrates on cell behaviour in vitro was assessed by measuring total protein in the cell lysate and the production of several phenotypic markers: collagen type I (COL 1), alkaline phosphatase (ALP), osteocalcin (OC), and the formation of bone mineral. After 7 days, β-glycerophosphate and physiological levels of hydrocortisone were added to the culture medium to stimulate cell differentiation and mineral production. There was a significantly higher production of ALP on 1.5 wt % Si-HA at day 7 following which, the addition of hydrocortisone promoted the differentiation of cells on the other two substrates. Hydrocortisone addition also decreased the production of OC. During the period, when hydrocortisone was present, no significant difference in behavior was seen between cells on Si-HA and HA; however, following removal of hydrocortisone, cells responded to 0.8 wt % Si-HA with a significant increase in protein production. Using fluorescence microscopy, nodular structures labeled with tetracycline were observed on the surface of all substrates after 21 days. These structures were deposited on areas of high cell density but were not related to the presence or level of silicon in the substrate. These results indicate that human osteoblasts are affected by the presence of silicon in the HA substrate and that the timing of these effects may be dependent upon the level of silicon substitution. © 2006 Wiley Periodicals, Inc.
Cited By (since 1996): 33Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30806PubMed ID: 16871624Language of Original Document: EnglishCorrespondence Address: Brooks, R.A.; Orthopaedic Research Unit, Box 180, Addenbrooke's Hospital, Hills Road, Cambridge CB2 3QZ, United Kingdom; email: rb10003@cam.ac.ukChemicals/CAS: alkaline phosphatase, 9001-78-9; glycerol 2 phosphate, 17181-54-3; hydrocortisone, 50-23-7; hydroxyapatite, 1306-06-5, 51198-94-8; osteocalcin, 136461-80-8; silicon, 7440-21-3; tetracycline, 23843-90-5, 60-54-8, 64-75-5; Collagen Type I; Durapatite, 1306-06-5; ectonucleotide pyrophosphatase phosphodiesterase 1, EC 3.1.4.1; Minerals; Osteocalcin, 104982-03-8; Phosphoric Diester Hydrolases, EC 3.1.4.-; Pyrophosphatases, EC 3.6.1.-; Silicon, 7440-21-3References: Hench, L., Splinter, R., Allan, W., Greenlee, T., Bonding mechanism at the interface of ceramic prosthetic materials (1972) J Biomed Mater Res, 2, pp. 117-141;Ducheyne, P., Hench, L., Kagan, A., Martens, M., Burssens, A., Mulier, J., The effect of hydroxyapatite impregnation on skeletal bonding of porous coated implants (1980) J Biomed Mater Res, 14, pp. 225-237; Jarcho, M., Calcium phosphates ceramics as hard tissue prosthetics (1981) Clin Orthop, 157, pp. 259-278; Nakamura, T., Yamamuro, T., Higashi, S., Kokubo, T., Ito, S., A new glass-ceramic for bone replacement: Evaluation of its bonding to bone tissue (1985) J Biomed Mater Res, 19, pp. 685-698; Ducheyne, P., Bianci, P., Radin, S., Schepers, E., Bioactive materials: Mechanism and bioengineering considerations (1993) Bone-Bioactive Biomaterials, pp. 1-12. , Ducheyne P, Kokubo T, van Blitterswijik C, editors. Leiderdorp, The Netherlands: Reed Healthcare Communications; Patel, N., Best, S., Gibson, I.R., Hing, K., Damien, K., Bonfield, W., A comparative study on the in vivo behaviour of hydroxyapatite and silicon substituted hydroxyapatite granules (2002) J Mater Sci Mater Med, 13, pp. 1199-1206; Jha, L., Best, S., Santos, J., Gibson, I., Bonfield, W., Silicon-substituted apatites and process for the preparation thereof Worldwide Patent,PCT/GB97/02325 and US Patent0.9/147773, 1999Gibson, I.R., Best, S.M., Bonfield, W., Chemical characterization of silicon-substituted hydroxyapatite (1999) J Biomed Mater Res, 44, pp. 422-428; Schwarz, K., Significance and functions of silicon in warm-blooded animals (1977) Proceedings of the 40th Nobel Symposium, , Bendz G, Lindquist I, editors. Biochemistry of Silicon and Related Problems. New York: Plenum; Lidingö, Sweden, August 23-26; Baxter, J., Rousseau, G., Benson, M., Garcea, R.L., Ito, J., Tomkins, G., Role of DNA and specific cytoplasmic receptors in glucocorticoid action (1972) Proc Natl Acad Sci USA, 69, p. 1892; Darley, W., Volcani, B., Role of silicon in diatom metabolism. A silicon requirement for deoxyribonucleic acid synthesis in diatom Cylindrotheca-fusiformis reimann and lewin (1969) Exp Cell Res, 58 (2-3), p. 334; Finkelstein, D., Butow, R., DNA-binding proteins in yeast. Effect of growth phase and mitochondrial-function (1976) Arch Biochem Biophys, 174, pp. 52-65; Volcani, B.E., Role of silicon in diatom metabolism and silicification (1977) Proceedings of the 40th Nobel Symposium, , Bendz G, Lindquist I, editors. Biochemistry of Silicon and Related Problems. New York: Plenum; Lidingo, Sweden, August 23-26; Werner, D., Regulation of metabolism by silicate in diatoms (1977) Proceedings of the 40th Nobel Symposium, , Bendz G, Lindquist I, editors. Biochemistry of Silicon and Related Problems. New York: Plenum; Lidingö, Sweden, August 23-26; Carlisle, E., Essentiality and function of silicon (1977) Proceedings of the 40th Nobel Symposium, , Bendz C, Lindquist I, editors. Biochemistry of Silicon and Related Problems New York: Plenum; Lidingo, Sweden, August 23-26; Carlisle, E., (1986) Silicon Biochemistry, , New York: Wiley; Schwarz, K., Milne, D., Growth-promoting effects of silicon in rats (1972) Nature, 239, p. 333; Seaborn, C., Nielsen, F., Dietary silicon affects acid and alkaline phosphatase and 45calcium uptake in bone of rats (1994) J Trace Elem Exp Med, 7, pp. 11-18; Reffitt, D., Ogston, N., Jugdaohsingh, R., Cheung, H., Evans, B., Thompson, R., Powell, J.J., Hampson, G.N., Orthosilicic acid stimulates collagen type I synthesis and osteoblastic differentiation in human osteoblast-like cells in vitro (2003) Bone, 32, p. 127; Shi, S., Kirk, M., Kahan, A., The role of type 1 collagen in the regulation of the osteoblast phenotype (1996) J Bone Miner Res, 11, pp. 1139-1145; Hildebrand, M., Higgins, D., Busser, K., Benjamin, E., Silicon-responsive cDNA clones isolated from the marine diatom Cylindrotheca fusiformis (1993) Gene, 132, pp. 213-218; Voronkov, M.G., Skorobogatova, V.J., Vugmeíster, E.K., Makarskii, V.V., Silicon in nuclei acids (1975) Dokl Biochem, 222, p. 29; Hench, L., Orcel, G., Physical-chemical and biochemical factors in silica sol-gel (1986) J Non-Cryst Solids, 82, pp. 1-10; Keting, P., Oursler, M., Wiegand, K., Bonde, S., Spelsberg, T., Riggs, L., Zeolite a increases proliferation, differentiation, and transforming growth factor production in normal adult human osteoblast-like cells in vitro (1992) J Bone Miner Res, 7, p. 1281; Gibson, I.R., Huang, J., Best, S.M., Bonfield, W., Enhanced in vitro cell activity and surface apatite layer formation on novel silicon-substituted hydroxyapatites (1999) Bioceramics, 12, pp. 191-194. , Ohgushi H, Hastings GW, Yoshikawa T, editors. Nara, Japan: World Scientific Publishing Company; Botelho, C.M., Brooks, R., Lopes, M.A., Santos, J.D., Best, S.M., Bonfield, W., Biological and physical-chemical characterization of phase pure HA and Si-substituted hydroxyapatite by different microscopy techniques (2004) Key Eng Mater, 254-256, pp. 845-848; Botelho, C.M., Stokes, D., Brooks, K., Best, S., Lopes, M., Santos, J.D., Effect of human serum proteins on the surface of pure HA and Si-substituted HA: AFM and ESEM studies (2003) Mater Sci Forum, 455-456, pp. 378-382; Sakobar, A., Millet, P., Myer, B., Rushton, N., A rapid, quantitative assay for measuring alkaline phosphatase activity in osteoblastic cells in vitro (1994) Bone Miner, 27, pp. 57-67; Botelho, C.M., Lopes, M.A., Gibson, I.R., Best, S.M., Santos, J.D., Structural analysis of Si-substituted hydroxyapatite: Zeta potential and X-ray photoelectron spectroscopy (XPS) (2002) J Mater Sci Mater Med, pp. 1123-1127; Lian, J., Stein, G., Aubin, J., Bone formation: Maturation and functional activities of osteoblast lineage cells (2003) Primer on the Metabolic Bone Diseases and Disorders of Mineral Metabolism, pp. 13-28. , Favus M, editor. Philadelphia: Lippincott; Boskey, A., Biomineralization: Conflicts, challenges and opportunities (1998) J Cell BiochemSuppl, 30-31, pp. 83-91; Jaiswal, N., Haynesworth, S., Caplan, A., Bruder, S., Osteogenic differentiation of purified culture-expanded human mesenchymal stem cells in vitro (1997) J Cell Biochem, 64, pp. 295-312; Baylink, D., Glucocorticoid-induced osteoporosis (1983) N Engl J Med, 309, pp. 306-308; Ireland, D., Bord, S., Beavan, S., Compston, J., Hydrocortisone increases the rate of differentiation of culture human osteoblasts (2004) J Cell Biochem, 91, pp. 594-601; Lian, J., Stein, G., Stein, J., Wijnen, A., Osteocalcin gene promoter: Unlocking the secrets for regulation of osteoblasts growth and differentiation (1998) J Cell BiochemSuppl, 30-31, pp. 62-72; Canalis, E., Mechanisms of glucocorticoid action in bone: Implications to glucocorticoid-induced osteoporosis (1995) J Clin Endocrinol Metab, 10, pp. 3441-3447; Delany, A., Gabbitas, B., Canalis, E., Cortisol down-regulates osteoblast α 1 (I) procollagen mRNA by transcriptional and post-transcriptional mechanisms (1995) J Cell Biochem, 57, pp. 488-494; Bellows, C., Aubin, J., Heersche, J., Physiological concentrations of glucocorticoids stimulate formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Cheng, S., Zhang, S., Mohan, S., Eecanda, E., Eausto, A., Hunt, A., Canalis, E., Avioli, L.V., Regulation of insulin-like growth factors I and II and their binding proteins in human bone marrow stromal cells by dexamethasone (1998) J Cell Biochem, 71, pp. 449-458; Boskey, A., Paschalis, E., Matrix proteins and biomineralization (1999) Bone Engineering, pp. 44-62. , Davie J, editor. Toronto: Em Squared; Shiga, M., Kapila, Y., Zhang, Q., Hayami, T., Kapila, S., Ascorbic acid induces collagenase-1 in human periondontal ligament cells but not in MC3T3-E1 osteoblast-like cells: Potential association between collagenase expression and changes in alkaline phosphatase phenotype (2003) J Bone Miner Res, 18, pp. 67-77; Franceschi, R., Iyer, B., Cui, Y., Effects of ascorbic acid on collagen matrix formation ans osteoblast differentiation of murine MC3T3-E1 cells (1994) J Bone Miner Res, 9, pp. 843-854; Franceschi, R., Iyer, B., Relationship between collagen synthesis and expression of the osteoblast phenotype in MC3T3-E1 cells (1992) J Bone Miner Res, 7, pp. 235-246; Aronow, M., Gerstenfeld, E., Owen, T., Tassinari, M., Stein, G., Lian, J., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J Cell Physiol, 143, pp. 213-221; Chien, H., Lin, W., Cho, M., Interkukin-1b-induced release of matrix proteins into culture media causes inhibition of mineralization of nodules formed by periodontal ligament cells in vitro (1999) Calcif Tissue Int, 64, pp. 402-413; Botelho, C.M., Brooks, R.A., Kawai, T., Ogata, S., Ohtsuki, C., Lopes, M.A., Best, S.M., Bonfield, W., In vitro analysis of proteins adhesion to phase pure hydroxyapatite and silicon-substituted hydroxyapatite (2005) Key Eng Mater, 17, pp. 461-464; Kaji, T., Kawatani, R., Takata, M., Hoshino, T., Miyahara, T., Kozuka, H., Koizumi, F., The effects of cadmium, copper or zinc on formation of embryonic chick bone in tissue culture (1988) Toxicology, 50, pp. 303-316
Keywords: alkaline phosphatase; article; Biomarkers; bone mineral; cell activity; Cell culture; cell density; cell differentiation; cell function; cell lysate; cell marker; cell protein; Cells; Cells, Cultured; collagen type 1; Collagen type I; culture medium; Durapatite; Fluorescence microscopy; glycerol 2 phosphate; hormone determination; human; human cell; Human osteoblasts; Humans; Hydrocortisone; hydroxyapatite; in vitro study; Minerals; Nodular mineral formation; osteoblast; Osteoblasts; osteocalcin; Osteocalcin (OC); phenotype; Phosphoric Diester Hydrolases; protein analysis; protein synthesis; Pyrophosphatases; Silicon; Substitution reactions; Substrates; Tetracycline; β-glycerophosphate

In vivo performance of biodegradable calcium phosphate glass ceramics using the rabbit model: Histological and SEM observation - Dias, A.G.; Lopes, M.A.; Santos, J.D.; Afonso, A.; Tsuru, K.; Osaka, A.; Hayakawa, S.; Takashima, S.; Kurabayashi, Y. (Journal of Biomaterials ApplicationsJ. Biomater. Appl., 2006)
Two MK5 (45CaO-45P 2O 5-5MGO-5K 2O, in mol% and MT13 (45CaO-37P 2O 5-5MgO-13TiO 2, in mol%) glasses are prepared in the meta- and pyrophosphate regions and crystallized to obtain MK5B and MT13B, respectively. MK5B was obtained by controlled crystallization, and MT13B by powder sintering. As a result of these heat treatment processes, the crystalline phases precipitated in the glassy matrix are KCa(PO 3) 3, β-Ca(PO 3) 2, β-Ca 2P 2O 7 and Ca 4P 6O 19 phases for MK5B and CaTi 4(PO 4) 6, TiP 2O 7, α- and β-Ca 2P 2O 7 phases for MT13B. To assess the in vivo biological behavior of these glass ceramics, a mixed granulometry in the range 250-355 μm and 355-425 μm with a ratio of 1/1 was implanted for 2, 4, and 12 weeks in the tibiae of Japanese white rabbits. The results showed that the in vivo behavior was strongly affected by their solubility. All implanted materials, MK5B and MT13B, and β-tricalcium phosphate (β-TCP) as control material, showed signs of degradation in vivo. However, the levels of degradation were quite different throughout the implantation periods. The highest degradation was observed for MK5B glass ceramic and the lowest for MT13B with β-TCP in-between. All implanted materials allow for new bone formation in the bone defect area. At the longest implantation period (12 weeks), the MT13B and β-TCP materials were almost completely surrounded by new bone tissue, whereas MK5B showed some unfilled spaces. This behavior is discussed in terms of the high degradation observed in previous studies. © 2006 SAGE Publications.
Cited By (since 1996): 10Export Date: 21 November 2012Source: ScopusCODEN: JBAPEdoi: 10.1177/0885328206052466Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Instituto de Engenharia Biomédica (INEB), Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; Bone Substitutes; calcium phosphate, 10103-46-5; Calcium Phosphates; CeramicsReferences: Parikh, S.N., Bone Graft Substitutes in Modern Orthopedics (2002) Orthopedics, 25 (11), pp. 1301-1309;Tomford, W.W., Bone Allografts: Past, Present and Future (2000) Cell and Tissue Banking, 1, pp. 105-109; Betz, R.R., Limitations of Autograft and Allograft: New Synthetic Solutions (2002) Orthopedics, 25 (5), pp. S561-S570; Lane, J.M., Tomin, E., Bostrom, M.P.G., Biosynthetic Bone Grafting, Clinical Orthopaedics and Related Research (1999) Supplement S, 367, pp. S107-S117; Gazdag, A.R., Lane, J.M., Glaser, D., Forster, R.A., Alternatives to Autogenous Bone Graft: Efficacy and Indications (1995) Journal of the American Academy of Orthopaedic Surgeons, 3 (1); Vaccaro, A.R., The Role of the Osteoconductive Scaffold in Synthetic Bone Grafts (2002) Orthopedics, 25 (5), pp. S571-S578; Damien, C.J., Parsons, J.R., Bone-Graft and Bone-Graft Substitutes - A Review of Current Technology and Applications (1991) Journal of Applied Biomaterials, 2 (3), pp. 187-208; Porter, A.E., Patel, N., Skepper, J.N., Best, S.M., Bonfield, W., Comparison of in vivo Dissolution Processes in Hydroxyapatite and Silicon-substituted Hydroxyapatite Bioceramics (2003) Biomaterials, 24 (25), pp. 4609-4620; Raynaud, S., Champion, E., Lafon, J.P., Bernache-Assollant, D., Calcium Phosphate Apatites with Variable Ca/P Atomic Ratio III Mechanical Properties and Degradation in Solution of Hot Pressed Ceramics (2002) Biomaterials 23, 4, pp. 1081-1089; Klein, C., Wolke, J.G.C., Deblieckhogervorst, J.M.A., Degroot, K., Features of Calcium-Phosphate Plasma-Sprayed Coatings - An in-vitro Study (1994) Journal of Biomedical Materials Research, 28 (8), pp. 961-967; Brow, R.K., Review: The Structure of Simple Phosphate Glasses (2000) Journal of Non-Crystalline Solids, 263 (1-4), pp. 1-28; Shelby, J.E., (1997) Introduction to Glass Science and Technology, , The Royal Society of Chemistry, UK; Fini, M., Giardino, R., In vitro and in vivo Tests for the Biological Evaluation of Candidate Orthopedic Materials: Benefits and Limits (2003) Journal of Applied Biomaterials & Biomechanics, 1, pp. 155-163; Ratner, B.D., Hoffman, A.S., Schoen, F.J., Lemons, F.J., (1996) Biomaterials Science: An Introduction to Materials in Medicine, , Academic Press; Dias, A.G., Lopes, M.A., Gibson, I.R., Santos, J.D., In vitro Degradation Studies of Calcium Phosphate Glass Ceramics Prepared by Controlled Crystallization (2003) Journal of Non-Crystalline Solids, 330 (1-3), pp. 81-89; Dias, A.G., Lopes, M.A., Santos, J.D., Protein Adsorption Effect on in vitro Acellular Biodegradation of CaO-P 2O 5 Glass Ceramics (2004) Advanced Materials Forum, 455-456, pp. 398-401; Dias, A.G., Skakle, J.M.S., Gibson, I.R., Lopes, M.A., Santos, J.D., In situ Thermal and Structural Characterization of Bioactive Calcium Phosphate Glass Ceramics Containing TiO 2 and MgO Oxides: HT-XRD Studies (2005) Journal of Non-Crystalline Solids, 351, pp. 810-817; Dias, A.G., Tsuru, K., Hayakawa, T., Lopes, M.A., Santos, J.D., Osaka, A., Crystallisation Studies of Biodegradable CaO-P 2O 5 Glass with MgO and TiO 2 for Bone Regeneration Applications (2004) Glass Technology, 45 (2), pp. 78-79; Gross, U., Muller-Mai, C., Voigt, C., Mesgarian, M., Berger, G., Ploska, U., Tissue Response in the Femur of Rabbits after Implantation of a New Calcium Titanium Phosphate Composition (2000) Key Engineering Materials, 192, pp. 383-386; Kitsugi, T., Yamamuro, T., Nakamura, T., Masanori, O., Transmission Electron Microscopy Observations at the Interface of Bone and Four Types of Calcium Phosphate Ceramics with Different Calcium/ Phosphorous Molar Ratios (1995) Biomaterials, 16 (14), pp. 1101-1107; Chun, S., Jeong, J.H., Kim, K-H., Kim, S., Biodegradation Study of Amorphous and Crystalline Calcium Metaphosphate in the SBF and Tris-buffer Solution (2000) Key Engineering Materials, 192, pp. 131-134; Chun, S., Na, S.W., Lee, J.H., Chung, J.P., Ryu, I.C., Kim, S.Y., Biodegradation Study of Potassium Calcium Metaphosphate in the SBF and Tris-buffer Solution (2002) Key Engineering Materials, 218, pp. 149-152; Lin, F.H., Liao, C.J., Chen, K.S., Sun, J.S., Liu, H.C., Degradation Behaviour of a New Bioceramic: Ca 2P 2O 7 with Addition of Na 4P 2O 7 · 10H 2O (1997) Biomaterials, 18 (13), pp. 915-921; Koerten, H.K., van der Meulen, J., Degradation of Calcium Phosphate Ceramics (1999) Journal of Biomedical Materials Research, 44 (1), pp. 78-86; Kwon, S.H., Jun, Y.K., Hong, S.H., Kim, H.E., Synthesis and Dissolution Behavior of Beta-TCP and HA/Beta-TCP Composite Powders (2003) Journal of the European Ceramic Society, 23 (7), pp. 1039-1045; Lu, J.X., Gallur, A., Flautre, B., Anselme, K., Descamps, M., Thierry, B., Comparative Study of Tissue Reactions to Calcium Phosphate Ceramics among Cancellous, Cortical, and Medullar Bone Sites in Rabbits (1998) Journal of Biomedical Materials Research, 42 (3), pp. 357-367; Yuan, H.P., De Bruijn, J.D., Li, Y.B., Feng, J.Q., Yang, Z.J., De Groot, K., Zhang, X.D., Bone Formation Induced by Calcium Phosphate Ceramics in Soft Tissue of Dogs: A Comparative Study Between Porous α-TCP and Β-TCP (2001) Journal of Materials Science-Materials in Medicine, 12 (1), pp. 7-13; Jiaxi, L., Michel, D., Jacques, D., Gilles, K., Pierre, H., Jacques, L., The Biodegradation Mechanism of Calcium Phosphate Biomaterials in Bone Journal of Biomedical Materials Research (Applied Biomaterials), 63, pp. 408-412; Legeros, R.Z., Biodegradation and Bioresorption of Calcium Phosphate Ceramics (1993) Clinic Materials, 14, pp. 65-88; Yli-Urpo, H., Vallittu, P.K., Narhi, T.O., Forsback, A.P., Vakiparta, M., Release of Silica, Calcium, Phosphorus, and Fluoride from Glass Ionomer Cement Containing Bioactive Glass (2004) Journal of Biomaterials Applications, 19 (1), pp. 5-20; John, A., Varma, H.K., Kumari, T.V., Surface Reactivity of Calcium Phosphate based Ceramics in a Cell Culture System (2003) Journal of Biomaterials Applications, 18 (1), pp. 63-78; Dias, A.G., Lopes, M.A., Gibson, I.R., Skakle, J.M.S., Tsuru, K., Hayakawa, S., Osaka, A., Santos, J.D., Studies of Calcium Phosphate Glass Ceramic Containing TiO 2 and MgO Ions: Dissolution Behavior, , vitro (submitted)
Keywords: Absorbable Implants; animal; Animals; article; Biodegradable glass ceramics; biodegradable implant; Biodegradation; bone prosthesis; Bone Substitutes; bone tissue; Calcium Compounds; calcium phosphate; Calcium phosphates; ceramics; chemistry; disease model; Disease Models, Animal; glass; Glass ceramics; histology; Imaging techniques; In vivo testing; materials testing; Optical microscopy; Pathology; rabbit; Rabbits; Scanning electron microscopy; tibia fracture; Tibial Fractures; Tissue; treatment outcome; X ray diffraction analysis

A model for educational simulation of neonatal cardiovascular pathophysiology. - Sá Couto, C.D.; van Meurs, W.L.; Goodwin, J.A.; Andriessen, P. (Simulation in healthcare : journal of the Society for Simulation in HealthcareSimul Healthc, 2006)
Full-body patient simulators provide a technological basis for clinical education without risk to real patients. In a previous study, we described a model for educational simulation of infant cardiovascular physiology. Using essentially the same methodology, we derive a mathematical model for the cardiovascular system of a healthy 1-week-old neonate. Computer simulations of this model result in vital signs that are close to target hemodynamic variables. Simulated systemic arterial pressure waveform and left ventricular pressure-volume loop are realistic, and the system reacts appropriately to blood loss. We also adapt the model structure and change its parameters to reflect the congenital heart defects: patent ductus arteriosus, tetralogy of Fallot, complex coarctation of the aorta with patent foramen ovale, and transposition of the great arteries. Simulated vital signs are again close to target hemodynamic variables. The resulting model for neonatal cardiovascular pathophysiology is an essential step in attaining a full-body, model-driven neonatal acute care simulator.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusPubMed ID: 19088566Language of Original Document: EnglishCorrespondence Address: Sá Couto, C.D.
Keywords: article; cardiovascular disease; Cardiovascular Diseases; cardiovascular function; Cardiovascular Physiological Phenomena; cardiovascular system; Computer simulation; congenital heart malformation; Education, Medical, Graduate; educational model; Heart Defects, Congenital; human; Humans; infant welfare; Infant, Newborn; medical education; methodology; Models, Educational; Models, Theoretical; newborn; theoretical model

Modular neural network task decomposition via entropic clustering - Santos, J.M.; Alexandre, L.A.; De Sá, J.M. (Proceedings - ISDA 2006: Sixth International Conference on Intelligent Systems Design and ApplicationsProc. ISDA Sixth Int. Conf. Intelligent Syst. Design Applic., 2006)
The use of monolithic neural networks (such as a multilayer perceptron) has some drawbacks: e.g. slow learning, weight coupling, the black box effect. These can be alleviated by the use of a modular neural network. The creation of a MNN has three steps: task decomposition, module creation and decision integration. In this paper we propose the use of an entropie clustering algorithm as a way of performing task decomposition. We present experiments on several real world classification problems that show the performance of this approach. © 2006 IEEE.
Conference code: 69992Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusArt. No.: 4021410doi: 10.1109/ISDA.2006.198Language of Original Document: EnglishCorrespondence Address: Santos, J.M.; Instituto Superior de Engenharia do Porto, Instituto de Engenharia Biomédica, Porto, Portugal; email: jms@isep.ipp.ptReferences: Santos, J.M., Marques de Sá, J., Alexandre, L.A., LEGClust - a clustering algorithm based on layered entropie subgraphs (2005) IEEE Transactions on Pattern Analysis and Machine Intelligence, , submitted;Bauer, E., Kohavi, R., An empirical comparison of voting classification algorithms: Bagging, boosting, and variants (1999) Machine Learning, 36 (1-2), pp. 105-139; Dietterich, T.G., An experimental comparison of three methods for constructing ensembles of decision trees: Bagging, boosting, and randomization (2000) Machine Learning, 40 (2), pp. 139-157; Kittler, J., Hatef, M., Duin, R.P.W., Matas, J., On combining classifiers (1998) IEEE Trans. Pattern Anal. Mach. Intell, 20 (3), pp. 226-239; Allwein, E.L., Schapire, R.E., Singer, Y., Reducing multiclass to binary: A unifying approach for margin classifiers (2000) Proc. 17th International Conf on Machine Learning, pp. 9-16. , Morgan Kaufmann, San Francisco, CA; Alexandre, L.A., Campilho, A.C., Kamel, M., Bounds for the average generalization error of the mixture of experts neural network (2004) LNCS, 3138, pp. 618-625. , 5th International Workshop on Statistical Techniques in Pattern Recognition; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, 3, pp. 79-87; Auda, G., Kamel, M., Modular neural network classifiers: A comparative study (1998) Intel. Robotic Systems, 21, pp. 117-129; Jordan, M., Jacobs, R., Hierarchical mixture of experts and the EM algorithm (1994) Neural Computation, 6, pp. 181-214; Jacobs, R., Peng, F., Tanner, M., A bayesian approach to model selection in hierarchical mixtures-of-experts architectures (1997) Neural Networks, 10 (2), pp. 231-241; Vilalta, R., Achari, M.K., Eick, C.F., Class decomposition via clustering: A new framework for lowvariance classifiers (2003) Third IEEE International Conference on Data Mining, pp. 673-676; Alexandre, L.A., Campilho, A.C., Kamel, M., A probabilistic model for the cooperative modular neural network (2003) LNCS, 2652, pp. 11-18. , Proceedings of the IbPRIA 2003; Ennaji, A., Ribert, A., Lecourtier, Y., From data topology to a modular classifier (2003) International Journal on Document Analysis and Recognition, 6 (1), pp. 1-9; Ng, A.Y., Jordan, M.I., Weiss, Y., On spectral clustering: Analysis and an algorithm (2001) Advances in Neural Information Processing Systems, 14; Bowman, A.W., Azzalini, A., (1997) Applied Smooting Techniques for Data Analysis, , London:Oxford University Press; Marques de Sá, J., (2003) Applied statistics using SPSS, STATISTICA andMATLAB, , Springer; Blake, C., Keogh, E., Merz, C., (1998) UCI repository of machine learning databases; Forina, M., Armanino, C., Eigenvector projection and simplified non-linear mapping of fatty acid content of Italian olive oils (1981) Ann. Chim. (Rome), 72, pp. 127-155
Keywords: Classification (of information); Clustering algorithms; Decision Theory; Entropic clustering; Learning systems; Modular neural network task decomposition; Monolithic neural networks; Neural networks; Weight coupling

New developments of the Z-EDM algorithm - Silva, L.M.; Marques de Sá, J.; Alexandre, L.A. (Proceedings - ISDA 2006: Sixth International Conference on Intelligent Systems Design and ApplicationsProc. ISDA Sixth Int. Conf. Intelligent Syst. Design Applic., 2006)
In this paper we address some open questions on the recently proposed Zero-Error Density Maximization algorithm for MLP training. We propose a new version of the cost function that solves a training problem encountered in previous work and prove that the use of a nonparametric density estimator preserves the optimal solution. Some experiments are reported comparing this cost function to the usual mean-square error and cross entropy cost junctions. © 2006 IEEE.
Conference code: 69992Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusArt. No.: 4021587doi: 10.1109/ISDA.2006.204Language of Original Document: EnglishCorrespondence Address: Silva, L.M.; INEB - Instituto de Engenharia Biomédica, Porto, Portugal; email: lmsilva@fe.up.ptReferences: Bishop, C., (1995) Neural Networks for Pattern Recognition, , Oxford University Press;Blake, C., Merz, C., (1998) UCI Repository of machine learning databases University of California, , http://www.ics.uci.edu/~mlearn/MLRepository.html, Irvine, Dept. of Information and Computer Sciences; Erdogmus, D., Principe, J.C., An Error-Entropy Minimization Algorithm for Supervised Training of Nonlinear Adaptive Systems (2002) IEEE Transactions on Signal Processing, 50 (7), pp. 1780-1786; Forina, M., Armanino, C., Eigenvector projection and simplified non-linear mapping of fatty acid content of Italian olive oils (1981) Ann. Chim. (Rome), 50, pp. 127-155; Marques de Sá, J., (2001) Pattern Recognition: Concepts, Methods and Applications, , Springer Verlag; J. Santos, L. Alexandre, and J. Marques de Sá. The Error Entropy Minimization Algorithm for Neural Network Classification. In Int. Conf. on Recent Advances in Soft Computing, Nottingham, United Kingdom, 2004Silva, L., Alexandre, L., Marques de Sá, J., Neural network classification: Maximizing zero-error density (2005) LNCS, 3686, pp. 127-135. , ICAPR 2005; Silva, L., Marques de Sá, J., Alexandre, L., Neural Network Classification using Shannon's Entropy (2005) European Symposium on Artificial Neural Networks; Silverman, B., (1986) Density Estimation for Statistics and Data Analysis, , Chapman & Hall
Keywords: Algorithms; Cost functions; Mean square error; MLP training; Nonparametric density estimators; Optimization; Personnel training; Problem solving; Zero-Error Density Maximization algorithm

The N-terminal half of the peroxisomal cycling receptor Pex5p is a natively unfolded domain - Carvalho, A.F.; Costa-Rodrigues, J.; Correia, I.; Costa Pessoa, J.; Faria, T.Q.; Martins, C.L.; Fransen, M.; Sá-Miranda, C.; Azevedo, J.E. (Journal of Molecular BiologyJ. Mol. Biol., 2006)
Targeting of most newly synthesised peroxisomal matrix proteins to the organelle requires Pex5p, the so-called PTS1 receptor. According to current models of peroxisomal biogenesis, Pex5p interacts with these proteins in the cytosol, transports them to the peroxisomal membrane and catalyses their translocation across the membrane. Presently, our knowledge on the structural details behind the interaction of Pex5p with the cargo proteins is reasonably complete. In contrast, information regarding the structure of the Pex5p N-terminal half (a region containing its peroxisomal targeting domain) is still limited. We have recently observed that the Stokes radius of this Pex5p domain is anomalously large, suggesting that this portion of the protein is either a structured elongated domain or that it adopts a low compactness conformation. Here, we address this issue using a combination of biophysical and biochemical approaches. Our results indicate that the N-terminal half of Pex5p is best described as a natively unfolded pre-molten globule-like domain. The implications of these findings on the mechanism of protein import into the peroxisome are discussed. © 2005 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 34Export Date: 21 November 2012Source: ScopusCODEN: JMOBAdoi: 10.1016/j.jmb.2005.12.002PubMed ID: 16403517Language of Original Document: EnglishCorrespondence Address: Azevedo, J.E.; Instituto de Biologia Molecular e Celular, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jazevedo@ibmc.up.ptChemicals/CAS: Amino Acids; peroxisome-targeting signal 1 receptor; Receptors, Cytoplasmic and NuclearReferences: Brown, L.A., Baker, A., Peroxisome biogenesis and the role of protein import (2003) J. Cell. Mol. Med., 7, pp. 388-400;Heiland, I., Erdmann, R., Biogenesis of peroxisomes. Topogenesis of the peroxisomal membrane and matrix proteins (2005) FEBS J., 272, pp. 2362-2372; Lazarow, P.B., Peroxisome biogenesis: Advances and conundrums (2003) Curr. Opin. Cell Biol., 15, pp. 489-497; Moyersoen, J., Choe, J., Fan, E., Hol, W.G., Michels, P.A., Biogenesis of peroxisomes and glycosomes: Trypanosomatid glycosome assembly is a promising new drug target (2004) FEMS Microbiol. Rev., 28, pp. 603-643; Weller, S., Gould, S.J., Valle, D., Peroxisome biogenesis disorders (2003) Annu. Rev. Genomics Hum. Genet., 4, pp. 165-211; Gould, S.J., Keller, G.A., Hosken, N., Wilkinson, J., Subramani, S., A conserved tripeptide sorts proteins to peroxisomes (1989) J. Cell Biol., 108, pp. 1657-1664; Klein, A.T., Barnett, P., Bottger, G., Konings, D., Tabak, H.F., Distel, B., Recognition of peroxisomal targeting signal type 1 by the import receptor Pex5p (2001) J. Biol. Chem., 276, pp. 15034-15041; Lametschwandtner, G., Brocard, C., Fransen, M., Van Veldhoven, P., Berger, J., Hartig, A., The difference in recognition of terminal tripeptides as peroxisomal targeting signal 1 between yeast and human is due to different affinities of their receptor Pex5p to the cognate signal and to residues adjacent to it (1998) J. Biol. Chem., 273, pp. 33635-33643; Brocard, C., Kragler, F., Simon, M.M., Schuster, T., Hartig, A., The tetratricopeptide repeat-domain of the PAS10 protein of Saccharomyces cerevisiae is essential for binding the peroxisomal targeting signal-SKL (1994) Biochem. Biophys. Res. Commun., 204, pp. 1016-1022; Dodt, G., Braverman, N., Wong, C., Moser, A., Moser, H.W., Watkins, P., Mutations in the PTS1 receptor gene, PXR1, define complementation group 2 of the peroxisome biogenesis disorders (1995) Nature Genet., 9, pp. 115-125; Fransen, M., Brees, C., Baumgart, E., Vanhooren, J.C., Baes, M., Mannaerts, G.P., Van Veldhoven, P.P., Identification and characterization of the putative human peroxisomal C-terminal targeting signal import receptor (1995) J. Biol. Chem., 270, pp. 7731-7736; Gatto Jr., G.J., Geisbrecht, B.V., Gould, S.J., Berg, J.M., A proposed model for the PEX5-peroxisomal targeting signal-1 recognition complex (2000) Proteins: Struct. Funct. Genet., 38, pp. 241-246; Otera, H., Setoguchi, K., Hamasaki, M., Kumashiro, T., Shimizu, N., Fujiki, Y., Peroxisomal targeting signal receptor Pex5p interacts with cargoes and import machinery components in a spatiotemporally differentiated manner: Conserved Pex5p WXXXF/Y motifs are critical for matrix protein import (2002) Mol. Cell. Biol., 22, pp. 1639-1655; Terlecky, S.R., Nuttley, W.M., McCollum, D., Sock, E., Subramani, S., The Pichia pastoris peroxisomal protein PAS8p is the receptor for the C-terminal tripeptide peroxisomal targeting signal (1995) EMBO J., 14, pp. 3627-3634; Gatto Jr., G.J., Geisbrecht, B.V., Gould, S.J., Berg, J.M., Peroxisomal targeting signal-1 recognition by the TPR domains of human PEX5 (2000) Nature Struct. Biol., 7, pp. 1091-1095; Agne, B., Meindl, N.M., Niederhoff, K., Einwachter, H., Rehling, P., Sickmann, A., Pex8p: An intraperoxisomal organizer of the peroxisomal import machinery (2003) Mol. Cell., 11, pp. 635-646; Albertini, M., Girzalsky, W., Veenhuis, M., Kunau, W.H., Pex12p of Saccharomyces cerevisiae is a component of a multi-protein complex essential for peroxisomal matrix protein import (2001) Eur. J. Cell Biol., 80, pp. 257-270; Reguenga, C., Oliveira, M.E., Gouveia, A.M., Sa-Miranda, C., Azevedo, J.E., Characterization of the mammalian peroxisomal import machinery: Pex2p. Pex5p, Pex12p, and Pex14p are subunits of the same protein assembly (2001) J. Biol. Chem., 276, pp. 29935-29942; Huhse, B., Rehling, P., Albertini, M., Blank, L., Meller, K., Kunau, W.-H., Pex17p of Saccharomyces cerevisiae is a novel peroxin and component of the peroxisomal protein translocation machinery (1998) J. Cell Biol., 140, pp. 49-60; Liu, H., Tan, X., Russell, K.A., Veenhuis, M., Cregg, J.M., PER3, a gene required for peroxisome biogenesis in Pichia pastoris, encodes a peroxisomal membrane protein involved in protein import (1995) J. Biol. Chem., 270, pp. 10940-10951; Rehling, P., Skaletz-Rorowski, A., Girzalsky, W., Voorn-Brouwer, T., Fransen, M.M., Distel, B., Pex8p, an intraperoxisomal peroxin of Saccharomyces cerevisiae required for protein transport into peroxisomes binds the PTS1 receptor pex5p (2000) J. Biol. Chem., 275, pp. 3593-3602; Smith, J.J., Szilard, R.K., Marelli, M., Rachubinski, R.A., The peroxin Pex17p of the yeast Yarrowia lipolytica is associated peripherally with the peroxisomal membrane and is required for the import of a subset of matrix proteins (1997) Mol. Cell. Biol., 17, pp. 2511-2520; Waterham, H.R., Titorenko, V.I., Haima, P., Cregg, J.M., Harder, W., Veenhuis, M., The Hansenula polymorpha PER1 gene is essential for peroxisome biogenesis and encodes a peroxisomal matrix protein with both carboxy- and amino-terminal targeting signals (1994) J. Cell Biol., 127, pp. 737-749; Costa-Rodrigues, J., Carvalho, A.F., Gouveia, A.M., Fransen, M., Sa-Miranda, C., Azevedo, J.E., The N terminus of the peroxisomal cycling receptor, Pex5p, is required for redirecting the peroxisome-associated peroxin back to the cytosol (2004) J. Biol. Chem., 279, pp. 46573-46579; Dodt, G., Gould, S.J., Multiple, P.E.X., Genes are required for proper subcellular distribution and stability of Pex5p, the PTS1 receptor: Evidence that PTS1 protein import is mediated by a cycling receptor (1996) J. Cell Biol., 135, pp. 1763-1774; Gouveia, A.M., Guimaraes, C.P., Oliveira, M.E., Reguenga, C., Sa-Miranda, C., Azevedo, J.E., Characterization of the peroxisomal cycling receptor, Pex5p, using a cell-free in vitro import system (2003) J. Biol. Chem., 278, pp. 226-232; Oliveira, M.E., Gouveia, A.M., Pinto, R.A., Sa-Miranda, C., Azevedo, J.E., The energetics of Pex5p-mediated peroxisomal protein import (2003) J. Biol. Chem., 278, pp. 39483-39488; Glover, J.R., Andrews, D.W., Rachubinski, R.A., Saccharomyces cerevisiae peroxisomal thiolase is imported as a dimer (1994) Proc. Natl Acad. Sci. USA, 91, pp. 10541-10545; McNew, J.A., Goodman, J.M., An oligomeric protein is imported into peroxisomes in vivo (1994) J. Cell Biol., 127, pp. 1245-1257; Stewart, M.Q., Esposito, R.D., Gowani, J., Goodman, J.M., Alcohol oxidase and dihydroxyacetone synthase, the abundant peroxisomal proteins of methylotrophic yeasts, assemble in different cellular compartments (2001) J. Cell Sci., 114, pp. 2863-2868; Walton, P.A., Hill, P.E., Subramani, S., Import of stably folded proteins into peroxisomes (1995) Mol. Biol. Cell, 6, pp. 675-683; Saidowsky, J., Dodt, G., Kirchberg, K., Wegner, A., Nastainczyk, W., Kunau, W.H., Schliebs, W., The di-aromatic pentapeptide repeats of the human peroxisome import receptor PEX5 are separate high affinity binding sites for the peroxisomal membrane protein PEX14 (2001) J. Biol. Chem., 276, pp. 34524-34529; Schliebs, W., Saidowsky, J., Agianian, B., Dodt, G., Herberg, F.W., Kunau, W.H., Recombinant human peroxisomal targeting signal receptor PEX5. Structural basis for interaction of PEX5 with PEX14 (1999) J. Biol. Chem., 274, pp. 5666-5673; Costa-Rodrigues, J., Carvalho, A.F., Fransen, M., Hambruch, E., Schliebs, W., Sa-Miranda, C., Azevedo, J.E., Pex5p, the peroxisomal cycling receptor, is a monomeric non-globular protein (2005) J. Biol. Chem., 280, pp. 24404-24411; Elgersma, Y., Elgersma-Hooisma, M., Wenzel, T., McCaffery, J.M., Farquhar, M.G., Subramani, S., A mobile PTS2 receptor for peroxisomal protein import in Pichia pastoris (1998) J. Cell Biol., 140, pp. 807-820; Rehling, P., Marzioch, M., Niesen, F., Wittke, E., Veenhuis, M., Kunau, W.H., The import receptor for the peroxisomal targeting signal 2 (PTS2) in Saccharomyces cerevisiae is encoded by the PAS7 gene (1996) EMBO J., 15, pp. 2901-2913; Zhang, J.W., Lazarow, P.B., Peb1p (Pas7p) is an intraperoxisomal receptor for the NH2-terminal, type 2, peroxisomal targeting sequence of thiolase: Peb1p itself is targeted to peroxisomes by an NH2-terminal peptide (1996) J. Cell Biol., 132, pp. 325-334; Dodt, G., Warren, D., Becker, E., Rehling, P., Gould, S.J., Domain mapping of human PEX5 reveals functional and structural similarities to Saccharomyces cerevisiae Pex18p and Pex21p (2001) J. Biol. Chem., 276, pp. 41769-41781; Einwachter, H., Sowinski, S., Kunau, W.H., Schliebs, W., Yarrowia lipolytica Pex20p Saccharomyces cerevisiae Pex18p/Pex21p and mammalian Pex5pL fulfil a common function in the early steps of the peroxisomal PTS2 import pathway (2001) EMBO Rep., 2, pp. 1035-1039; Matsumura, T., Otera, H., Fujiki, Y., Disruption of the interaction of the longer isoform of Pex5p, Pex5pL, with Pex7p abolishes peroxisome targeting signal type 2 protein import in mammals. Study with a novel Pex5-impaired Chinese hamster ovary cell mutant (2000) J. Biol. Chem., 275, pp. 21715-21721; Gouveia, A.M., Guimaraes, C.P., Oliveira, M.E., Sa-Miranda, C., Azevedo, J.E., Insertion of Pex5p into the peroxisomal membrane is cargo protein-dependent (2003) J. Biol. Chem., 278, pp. 4389-4392; De La Torre, J.G., Hydrodynamics of segmentally flexible macromolecules (1994) Eur. Biophys. J., 23, pp. 307-322; Denning, D.P., Uversky, V., Patel, S.S., Fink, A.L., Rexach, M., The Saccharomyces cerevisiae nucleoporin Nup2p is a natively unfolded protein (2002) J. Biol. Chem., 277, pp. 33447-33455; Permyakov, S.E., Millett, I.S., Doniach, S., Permyakov, E.A., Uversky, V.N., Natively unfolded C-terminal domain of caldesmon remains substantially unstructured after the effective binding to calmodulin (2003) Proteins: Struct. Funct. Genet., 53, pp. 855-862; Uversky, V.N., Natively unfolded proteins: A point where biology waits for physics (2002) Protein Sci., 11, pp. 739-756; Lydakis-Simantiris, N., Hutchison, R.S., Betts, S.D., Barry, B.A., Yocum, C.F., Manganese stabilizing protein of photosystem II is a thermostable, natively unfolded polypeptide (1999) Biochemistry, 38, pp. 404-414; Sreerama, N., Woody, R.W., Estimation of protein secondary structure from circular dichroism spectra: Comparison of CONTIN, SELCON, and CDSSTR methods with an expanded reference set (2000) Anal. Biochem., 287, pp. 252-260; Stanley, W.A., Sokolova, A., Brown, A., Clarke, D.T., Wilmanns, M., Svergun, D.I., Synergistic use of synchrotron radiation techniques for biological samples in solution: A case study on protein-ligand recognition by the peroxisomal import receptor Pex5p (2004) J. Synchrotron Radiat., 11, pp. 490-496; Oberg, K.A., Fink, A.L., A new attenuated total reflectance Fourier transform infrared spectroscopy method for the study of proteins in solution (1998) Anal. Biochem., 256, pp. 92-106; Navea, S., Tauler, R., De Juan, A., Application of the local regression method interval partial least-squares to the elucidation of protein secondary structure (2005) Anal. Biochem., 336, pp. 231-242; Obradovic, Z., Peng, K., Vucetic, S., Radijovac, P., Dunker, A.K., Exploiting heterogeneous sequence properties improves prediction of protein disorder (2006) Proteins, , In the press; Gould, S.J., Collins, C.S., Opinion: Peroxisomal-protein import: Is it really that complex? (2002) Nature Rev. Mol. Cell. Biol., 3, pp. 382-389; Shoemaker, B.A., Portman, J.J., Wolynes, P.G., Speeding molecular recognition by using the folding funnel: The fly-casting mechanism (2000) Proc. Natl Acad. Sci. USA, 97, pp. 8868-8873; Pontius, B.W., Close encounters: Why unstructured, polymeric domains can increase rates of specific macromolecular association (1993) Trends Biochem. Sci., 18, pp. 181-186; Tompa, P., Intrinsically unstructured proteins (2002) Trends Biochem. Sci., 27, pp. 527-533; Gouveia, A.M., Reguenga, C., Oliveira, M.E., Sa-Miranda, C., Azevedo, J.E., Characterization of peroxisomal Pex5p from rat liver. Pex5p in the Pex5p-Pex14p membrane complex is a transmembrane protein (2000) J. Biol. Chem., 275, pp. 32444-32451; Dammai, V., Subramani, S., The human peroxisomal targeting signal receptor, Pex5p, is translocated into the peroxisomal matrix and recycled to the cytosol (2001) Cell, 105, pp. 187-196; Imanaka, T., Small, G.M., Lazarow, P.B., Translocation of acyl-CoA oxidase into peroxisomes requires ATP hydrolysis but not a membrane potential (1987) J. Cell Biol., 105, pp. 2915-2922; Wendland, M., Subramani, S., Cytosol-dependent peroxisomal protein import in a permeabilized cell system (1993) J. Cell Biol., 120, pp. 675-685; Azevedo, J.E., Costa-Rodrigues, J., Guimaraes, C.P., Oliveira, M.E., Sa-Miranda, C., Protein translocation across the peroxisomal membrane (2004) Cell Biochem. Biophys., 41, pp. 451-468; Wang, D., Visser, N.V., Veenhuis, M., Van Der Klei, I.J., Physical interactions of the peroxisomal targeting signal 1 receptor pex5p, studied by fluorescence correlation spectroscopy (2003) J. Biol. Chem., 278, pp. 43340-43345; Oliveira, M.E., Reguenga, C., Gouveia, A.M., Guimaraes, C.P., Schliebs, W., Kunau, W.H., Mammalian Pex14p: Membrane topology and characterisation of the Pex14p-Pex14p interaction (2002) Biochim. Biophys. Acta, 1567, pp. 13-22; Fransen, M., Wylin, T., Brees, C., Mannaerts, G.P., Van Veldhoven, P.P., Human pex19p binds peroxisomal integral membrane proteins at regions distinct from their sorting sequences (2001) Mol. Cell. Biol., 21, pp. 4413-4424; Sreerama, N., Venyaminov, S.Y., Woody, R.W., Estimation of protein secondary structure from circular dichroism spectra: Inclusion of denatured proteins with native proteins in the analysis (2000) Anal. Biochem., 287, pp. 243-251; Vigano, C., Margolles, A., Van Veen, H.W., Konings, W.N., Ruysschaert, J.M., Secondary and tertiary structure changes of reconstituted LmrA induced by nucleotide binding or hydrolysis. a Fourier transform attenuated total reflection infrared spectroscopy and tryptophan fluorescence quenching analysis (2000) J. Biol. Chem., 275, pp. 10962-10967; Laurent, T.C., Killander, J., Theory of gel filtration + its experimental verification (1964) J. Chromatog., 14, pp. 217-230;
Keywords: Amino acids; amino terminal sequence; article; biogenesis; Calorimetry, Differential Scanning; cell membrane; cell receptor; Chromatography, Gel; circular dichroism; cytosol; differential scanning calorimetry; human; Humans; infrared spectroscopy; matrix protein; Natively unfolded; Peroxisomal protein import; peroxisome; Pex5p; priority journal; Protein conformation; protein degradation; protein domain; protein folding; protein interaction; protein Pex5p; protein structure; Protein Structure, Secondary; Protein Structure, Tertiary; protein transport; pts1 receptor; PTS1-receptor; Receptors, Cytoplasmic and Nuclear; Spectroscopy, Fourier Transform Infrared; unclassified drug

Silicon addition to hydroxyapatite increases nanoscale electrostatic, van der Waals, and adhesive interactions - Vandiver, J.; Dean, D.; Patel, N.; Botelho, C.; Best, S.; Santos, J.D.; Lopes, M.A.; Bonfield, W.; Ortiz, C. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
The normal intersurface forces between nanosized probe tips functionalized with COO
Cited By (since 1996): 15Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30737PubMed ID: 16646067Language of Original Document: EnglishCorrespondence Address: Ortiz, C.; Department of Materials Science and Engineering, Massachusetts Institute of Technology, 77 Massachusetts Avenue, Cambridge, MA 02139, United States; email: coritz@mit.eduChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; silicon, 7440-21-3; thiol derivative, 13940-21-1; Biocompatible Materials; Durapatite, 1306-06-5; Silicon, 7440-21-3References: Carlisle, E.M., Silicon: A possible factor in bone calcification (1970) Science, 167, pp. 279-280;Gibson, I.R., Best, S.M., Bonfield, W., Chemical characterization of silicon-substituted hydroxyapatite (1999) J Biomed Mater Res, 44, pp. 422-428; Gibson, I.R., Best, S.M., Bonfield, W., Effect of silicon substitution on the sintering and microstructure of hydroxyapatite (2002) J Am Ceram Soc, 85, pp. 2771-2777; Legeros, R.Z., LeGeros, J.P., Dense hydroxyapatite (1993) An Introduction to Bioceramics, pp. 139-180. , Hench LL, Wilson J, editors. Singapore: World Scientific; Van Raemdonck, W., Ducheyne, P., De Meester, P., Calcium phosphate ceramics (1984) Metal and Ceramic Biomaterials, pp. 143-166. , Ducheyne P, Hastings G, editors. Boca Raton, FL: CRC Press; Botelho, C.M., Lopes, M.A., Gibson, I.R., Best, S.M., Santos, J.D., Structural analysis of Si-substituted hydroxyapatite: Zeta potential and X-ray photoelectron spectroscopy (2002) J Mater Sci: Mater Med, 13, pp. 1123-1127; Gibson, I.R., Huang, J., Best, S.M., Bonfield, W., Enhanced in vitro cell activity and surface apatite layer formation on novel silicon-substituted hydroxyapatites (1999) Proceedings of the International Symposium on Ceramics in Medicine, Bioceramics 12, pp. 191-194. , Ohgushi H, Hastings GW, Yoshikawa T, editors. River Edge, NJ: World Scientific Publishing; Balas, F., Perez-Pariente, J., Vallet-Regi, M., In vitro bioactivity of silicon-substituted hydroxyapatites (2003) J Biomed Mater Res A, 66, pp. 364-375; Botelho, C.M., Brooks, R.A., Best, S.M., Lopes, M.A., Santos, J.D., Rushton, N., Bonfield, W., Biological and physical-chemical characterization of phase pure HA and Si-substituted hydroxyapatite by different microscopy techniques (2004) Proceedings of the International Symposium on Ceramics in Medicine, Bioceramics 16, pp. 845-848. , Barbosa MA, Monteiro FJ, Correia R, Leon B, editors. Uetikon-Zuerich, Switzerland: Trans Tech; Patel, N., Best, S.M., Bonfield, W., Gibson, I.R., Hing, K.A., Damien, E., Revel, P.A., A comparative study on the in vivo behavior of hydroxyapatite and silicon substituted hydroxyapatite granules (2002) J Mater Sci: Mater Med, 13, pp. 1199-1206; Porter, A.E., Patel, N., Skepper, J.N., Best, S.M., Bonfield, W., Effect of sintered silicate-substituted hydroxyapatite on remodeling process at the bone-implant interface (2004) Biomaterials, 25, pp. 3303-3314; Vandiver, J., Dean, D., Patel, N., Bonfield, W., Ortiz, C., Nanoscale variation in surface charge of synthetic hydroxyapatite detected by chemically and spatially specific high resolution force spectroscopy (2005) Biomaterials, 26, pp. 271-283; Ducheyne, P., Qiu, Q., Bioactive ceramics: The effect of surface reactivity on bone formation and bone cell function (1999) Biomaterials, 20, pp. 2287-2303; Dubok, V.A., Bioceramics - Yesterday, today, tomorrow (2000) Powder Metall Met Ceram, 39, pp. 381-394; Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, V.C.A., The ultrastructure of the bone-hydroxyapatite interface in vitro (1992) J Biomed Mater Res, 26, pp. 1365-1382; Neo, M., Nakamura, T., Ohtsuki, C., Kokubo, T., Yamamuro, T., Apatite formation on three kinds of bioactive material at an early stage in vivo: A comparative study by transmission electron microscopy (1993) J Biomed Mater Res, 27, pp. 999-1006; Kokubo, T., Kushitani, H., Sakka, S., Kitsugi, T., Yamamuro, T., Solutions able to reproduce in vivo surface-structure changes in bioactive glass-ceramic A-W (1990) J Biomed Mater Res, 24, pp. 721-734; Himeno, T., Kim, H.-M., Kaneko, H., Kawashita, M., Kokubo, T., Nakamura, T., Surface structural changes of sintered hydroxyapatite in terms of surface charge (2003) Proceedings of the International Symposium on Ceramics in Medicine, Bioceramics 15, pp. 457-460. , Besim Ben-Nissan DS, William Walsh, editors. Uetikon-Zuerich, Switzerland: Trans Tech; Sato, K., Kumagai, Y., Tanaka, J., Apatite formation on organic monolayers in simulated body environment (2000) J Biomed Mater Res, 50, pp. 16-20; Tanahashi, M., Matsuda, T., Surface functional group dependence on apatite formation on self-assembled monolayers in a simulated body fluid (1997) J Biomed Mater Res, 34, pp. 305-315; Yamashita, K., Oikawa, N., Umegaki, T., Acceleration and deceleration of bone-like crystal growth on ceramic hydroxyapatite by electric poling (1996) Chem Mater, 8, pp. 2697-2700; Hwang, K.S., Song, J.E., Jo, J.W., Yang, H.S., Park, Y.J., Ong, J.L., Rants, H.R., Effect of poling conditions on growth of calcium phosphate crystal in ferroelectric BaTiO 3 ceramics (2002) J Mater Sci: Mater Med, 13, pp. 133-138; Ohgaki, M., Kizuki, T., Katsura, M., Yamashita, K., Manipulation of selective cell adhesion and growth by surface charges of electrically polarized hydroxyapatite (2001) J Biomed Mater Res, 57, pp. 366-373; Kobayashi, T., Nakamura, S., Yamashita, K., Enhanced osteobonding by negative surface charges of electrically polarized hydroxyapatite (2001) J Biomed Mater Res, 57, pp. 477-484; Parsegian, V.A., Gingell, D., On the electrostatic interaction across a salt solution between two bodies bearing unequal charges (1972) Biophys J, 12, pp. 1192-1204; Butt, H.J., Measuring electrostatic, van der Waals, and hydration forces in electrolyte-solutions with an atomic force microscope (1991) Biophys J, 60, pp. 1438-1444; Brown, P.W., Martin, R.I., An analysis of hydroxyapatite surface layer formation (1999) J Phys Chem B, 103, pp. 1671-1675; Noy, A., Vezenov, D.V., Lieber, C.M., Chemical force microscopy (1997) Annu Rev Mater Sci, 27, pp. 381-421; Israelachvili, J., (1991) Intermolecular and Surface Forces, , Amsterdam: Academic Press; Verwey, E.J.W., Overbeek, J.T.G., Nes, K.V., (1948) Theory of the Stability of Lyophobic Colloids, , New York: Elsevier; Akao, M., Aoki, H., Kato, K., Mechanical properties of sintered hydroxyapatite for prosthetic applications (1981) J Mater Sci, 16, pp. 809-812; Seog, J., Dean, D., Plass, A.H.K., Wong-Palms, S., Grodzinsky, A.J., Ortiz, C., Direct measurement of glycosaminoglycan intermolecular interactions via high-resolution force spectroscopy (2002) Macromolecules, 35, pp. 5601-5615; Ashby, P.D., Chen, L., Lieber, C.M., Probing intermolecular forces and potentials with magnetic feedback chemical force microscopy (2000) J Am Chem Soc, 122, pp. 9467-9472; Ederth, T., Computation of Lifshitz-van de Waals forces between alkylthiol monolayers on gold films (2001) Langmuir, 17, pp. 3329-3340; Forsythe, G.E., Wasow, W.R., (1960) Finite Difference Methods for Partial Differential Equations, , New York: Wiley; (1997) Principles of Colloid and Surface Chemistry, 3rd Ed., , Hiemenz P, Rajagopalan R, editors. New York: Marcel Dekker; Eichert, D., Combes, C., Drouet, C., Rey, C., Formation and evolution of hydrated surface layers of apatites (2005) Proceedings of the International Symposium on Ceramics in Medicine, Bioceramics 17, pp. 3-6. , Li P, Zhang K, Colwell C, editors. Uetikon-Zuerich, Switzerland: Trans Tech; Rixman, M., Dean, D., Macias, C., Ortiz, C., Nanoscale intermolecular interactions between human serum albumin and alkanethiol self-assembled monolayers (2003) Langmuir, 19, pp. 6202-6218; Ackler, H.D., French, R.H., Chiang, Y., Comparisons of Hamaker constants for ceramic systems with intervening vacuum or water: From force laws and physical properties (1996) J Colloid Interface Sci, 179, pp. 460-469; Kane, V., Mulvaney, P., Double-layer interactions between self-assembled monolayers of ω-mercaptoundecanoic acid on gold surfaces (1998) Langmuir, 14, pp. 3302-3311; Atkins, P., (1997) The Elements of Physical Chemistry, , New York: Freeman; Zhu, P.X., Masuda, Y., Koumoto, K., Site-selective adhesion of hydroxyapatite microparticles on charged surfaces in a super-saturated solution (2001) J Colloid Interface Sci, 243, pp. 31-36; James, M., Hunter, R.J., O'Brien, R.W., Effect of particle size distribution and aggregation on electroacoustic measurements of ξ potential (1992) Langmuir, 8, pp. 420-423; Toikka, G., Hayes, R.A., Ralston, J., Surface forces between spherical ZnS particles in aqueous electrolyte (1996) Langmuir, 12, pp. 3783-3788; Pedersen, H.G., Bergstrom, L., Forces measured between zirconia surfaces in poly(acrylic acid) solutions (1999) J Am Ceram Soc, 82, pp. 1137-1145; Cohen, M., Joester, D., Geiger, B., Addadi, L., Spatial and temporal sequence of events in cell adhesion: From molecular recognition to focal adhesion assembly (2004) Chem Bio Chem, 5, pp. 1393-1399; Smith, I.O., Baumann, M.J., McCabe, L.R., Electrostatic interactions as a predictor for osteoblast attachment to biomaterials (2004) J Biomed Mater Res A, 70, pp. 436-441; (1979) Plasma Proteins, , Blombaek B, Hanson L, editors. New York: Wiley; Porter, A.E., Hobbs, L.W., Rosen, V.B., Spector, M., The ultrastructure of the plasma-sprayed hydroxyapatite-bone interface predisposing to bone bonding (2002) Biomaterials, 23, pp. 725-733; Porter, A.E., Patel, N., Skepper, J.N., Best, S.M., Bonfield, W., Comparison of in vivo dissolution processes in hydroxyapatite and silicon-substituted hydroxyapatite bioceramics (2003) Biomaterials, 24, pp. 4609-4620
Keywords: Adhesives; article; Atomic force microscopy; Biocompatible Materials; biomaterial; Biomaterials; Bone; cell adhesion; chemical binding; chemical interaction; derjaguin landau verwey overbeek approximation; Durapatite; electrochemical analysis; Electrostatic; Electrostatics; high resolution force spectroscopy; hydroxyapatite; materials testing; mathematical analysis; Microscopy, Electron, Scanning; Monolayers; Nanomechanics; Nanostructures; Particle Size; Poisson distribution; Polycrystalline materials; Silicon; Silicon-substituted hydroxyapatite; Spectrophotometry; Spectroscopy; Spectroscopy, Fourier Transform Infrared; Stress, Mechanical; Surface charge; surface property; thiol derivative; Van der Waals; Van der Waals forces

Three-dimensional culture of human osteoblastic cells in chitosan sponges: The effect of the degree of acetylation - Amaral, I.F.; Sampaio, P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
In this investigation, the effect of the degree of acetylation (DA) of chitosan on the behavior of human osteoblastic MG-63 cells cultured in three-dimensional chitosan matrices was assessed. Chitosan sponges with DAs in the range of 4 to 49% were prepared and characterized in terms of microstructure, porosity, and pore size. Collagen sponges were used as 3D control. Cell proliferation was determined using the MTT assay while the retention of the osteoblastic phenotype was monitored by assaying alkaline phosphatase activity. Cell morphology, cytoskeletal organization, and viability were assessed using different microscopy techniques. Chitosan sponges showed a similar microstructure regardless the DA, except for the highest DA used, where a more heterogeneous pore distribution was observed. In terms of cell proliferation, alkaline phosphatase activity and cell viability, cells cultured in chitosan scaffolds performed as well as in the 3D control regardless the DA, except for the highest DA used, where an inhibitory effect on cell proliferation was found. However, while in sponges with DAs ≤ 13% cells attached and spread displaying long cell filopodia and numerous cell-to-cell contacts, in sponges with higher DAs cells tended to remain spherical and grow into spheroid-like cellular aggregates. In the present study, the DA played a key role in determining the affinity of osteoblastic cells towards the substrates, possibly by influencing the nature of the initial adsorbed protein layer. © 2005 Wiley Periodicals, Inc.
Cited By (since 1996): 19Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30522PubMed ID: 16270345Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; chitosan, 9012-76-4; collagen, 9007-34-5; Alkaline Phosphatase, EC 3.1.3.1; Chitosan, 9012-76-4; Collagen, 9007-34-5References: Bruder, S.P., Caplan, A.I., Bone regeneration through cellular engineering (2000) Principles of Tissue Engineering, pp. 683-696. , Lanza RP, Langer R, Vacanti J, editors. San Diego: Academic Press;Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681; Khor, E., (2001) Chitin: Fulfilling a Biomaterials Promise, , Oxford, UK: Elsevier Science Ltd; Vandevord, P.J., Hwt, M., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., Evaluation of the biocompatibility of a chitosan scaffold in mice (2002) J Biomed Mater Res, 59, pp. 585-590; Tomihata, K., Ikada, Y., In vitro and in vivo degradation of films of chitin and its deacetylated derivatives (1997) Biomaterials, 18, pp. 567-575; Rao, S.B., Sharma, C.P., Sterilization of chitosan: Implications (1995) J Biomater Appl, 10, pp. 136-143; Muzzarelli, R.A.A., Zucchini, C., Ilari, P., Pugnaloni, A., Belmonte, M.M., Biagini, G., Castaldini, C., Osteoconductive properties of methylpyrrolidinone chitosan in an animal-model (1993) Biomaterials, 14, pp. 925-929; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., Enhanced bone formation by controlled growth factor delivery from chitosan-based biomaterials (2002) J Control Release, 78, pp. 187-197; Zhao, F., Yin, Y.J., Lu, W.W., Leong, J.C., Zhang, W.J., Zhang, J.Y., Zhang, M.F., Yao, K.D., Preparation and histological evaluation of biomimetic three-dimensional hydroxyapatite/chitosan-gelatin network composite scaffolds (2002) Biomaterials, 23, pp. 3227-3234; Nettles, D.L., Elder, S.H., Gilbert, J.A., Potential use of chitosan as a cell scaffold material for cartilage tissue engineering (2002) Tissue Eng, 8, pp. 1009-1016; Zhang, Y., Zhang, M.Q., Calcium phosphate/chitosan composite scaffolds for controlled in vitro antibiotic drug release (2002) J Biomed Mater Res, 62, pp. 378-386; Prasitsilp, M., Jenwithisuk, R., Kongsuwan, K., Damrongchai, N., Watts, P., Cellular responses to chitosan in vitro: The importance of deacetylation (2000) J Mater Sci Mater Med, 11, pp. 773-778; Chatelet, C., Damour, O., Domard, A., Influence of the degree of acetylation on some biological properties of chitosan films (2001) Biomaterials, 22, pp. 261-268; Dhiman, H.K., Ray, A.R., Panda, A.K., Characterization and evaluation of chitosan matrix for in vitro growth of MCF-7 breast cancer cell lines (2004) Biomaterials, 25, pp. 5147-5154; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., Rat bone marrow stromal cells osteogenic differentiation and fibronectin adsorption on chitosan membranes: The effect of the degree of acetylation (2005) J Biomed Mater Res Part A, 75 A, pp. 387-397; Cukierman, E., Pankov, R., Stevens, D.R., Yamada, K.M., Taking cell-matrix adhesions to the third dimension (2001) Science, 294, pp. 1708-1712; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Mima, S., Miya, M., Iwamoto, R., Yoshikawa, S., Highly deacetylated chitosan and its properties (1983) J Appl Polym Sci, 28, pp. 1909-1917; Aiba, S., Studies on Chitosan: 1. Determination of the degree of N-acetylation of chitosan by ultraviolet spectrophotometry and gel-permeation chromatography (1986) Int J Biol Macromol, 8, pp. 173-176; Hirano, S., Ohe, Y., Ono, H., Selective N-acylation of chitosan (1976) Carbohydr Res, 47, pp. 315-320; Baxter, A., Dillon, M., Taylor, K.D.A., Roberts, G.A.F., Improved method for Ir determination of the degree of N-acetylation of chitosan (1992) Int J Biol Macromol, 14, pp. 166-169; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., Molecular parameters of chitosans depolymerized with the aid of papain (1996) Carbohydr Polym, 29, pp. 63-68; Zhang, R.Y., Ma, P.X., Poly(alpha-hydroxyl acids) hydroxyapatite porous composites for bone-tissue engineering. I. Preparation and morphology (1999) J Biomed Mater Res, 44, pp. 446-455; Mosmann, T., Rapid colorimetric assay for cellular growth and survival: Application to proliferation and cytotoxicity assays (1983) J Immunol Methods, 65, pp. 55-63; Ashton, B.A., Abdullah, F., Cave, J., Williamson, M., Sykes, B.C., Couch, M., Poser, J.W., Characterization of cells with high alkaline-phosphatase activity derived from human-bone and marrow - Preliminary assessment of their osteogenicity (1985) Bone, 6, pp. 313-319; Kurita, K., Controlled functionalization of the polysaccharide chitin (2001) Prog Polym Sci, 26, pp. 1921-1971; Wang, W., Bo, S.Q., Li, S.Q., Qin, W., Determination of the Mark-Houwink equation for chitosans with different degrees of deacetylation (1991) Int J Biol Macromol, 13, pp. 281-285; Roberts, G.A.F., (1992) Chitin Chemistry, , Houndmills: The Macmillan Press Ltd; Ueda, H., Hong, L., Yamamoto, M., Shigeno, K., Inoue, M., Toba, T., Yoshitani, M., Shimizu, Y., Use of collagen sponge incorporating transforming growth factor-beta 1 to promote bone repair in skull defects in rabbits (2002) Biomaterials, 23, pp. 1003-1010; Hanthamrongwit, M., Grant, M.H., Wilkinson, R., Confocal laser-scanning microscopy (Clsm) for the study of collagen sponge microstructure (1994) J Biomed Mater Res, 28, pp. 213-216; Zinger, O., Anselme, K., Denzer, A., Habersetzer, P., Wieland, M., Jeanfils, J., Hardouin, P., Landolt, D., Time-dependent morphology and adhesion of osteoblastic cells on titanium model surfaces featuring scale-resolved topography (2004) Biomaterials, 25, pp. 2695-2711; Eggli, P.S., Muller, W., Schenk, R.K., Porous hydroxyapatite and tricalcium phosphate cylinders with 2 different pore-size ranges implanted in the cancellous bone of rabbits - A comparative histomorphometric and histologic-study of bony ingrowth and implant substitution (1988) Clin Orthop, 232, pp. 127-138; Madihally, S.V., Matthew, H.W.T., Porous chitosan scaffolds for tissue engineering (1999) Biomaterials, 20, pp. 1133-1142; Madihally, S.V., Frattaroli, T.L., Matthew, H.W.T., (1999) In Vivo Colonization of Chitosan Based Porous Scaffolds, p. 172. , Providence, RI: Transactions from the 25th Annual Meeting of the Society for Biomaterials, Providence, RI; Zhang, Y., Zhang, M.Q., Synthesis and characterization of macroporous chitosan/calcium phosphate composite scaffolds for tissue engineering (2001) J Biomed Mater Res, 55, pp. 304-312; Chung, T.W., Yang, J., Akaike, T., Cho, K.Y., Nah, J.W., Kim, S.I., Cho, C.S., Preparation of alginate/galactosylated chitosan scaffold for hepatocyte attachment (2002) Biomaterials, 23, pp. 2827-2834; Masi, L., Franchi, A., Santucci, M., Danielli, D., Arganini, L., Giannone, V., Formigli, L., Beghe, F., Adhesion, growth, and matrix production by osteoblasts on collagen substrata (1992) Calcif Tissue Int, 51, pp. 202-212; Wiesmann, H.P., Nazer, N., Klatt, C., Szuwart, T., Meyer, U., Bone tissue engineering by primary osteoblast-like cells in a monolayer system and 3-dimensional collagen gel (2003) J Oral Maxillofac Surg, 61, pp. 1455-1462; Henriksen, I., Green, K.L., Smart, J.D., Smistad, G., Karlsen, J., Bioadhesion of hydrated chitosans: An in vitro and in vivo study (1996) Int J Pharmaceut, 145, pp. 231-240; Lebaron, R.G., Athanasiou, K.A., Extracellular matrix cell adhesion peptides: Functional applications in orthopedic materials (2000) Tissue Eng, 6, pp. 85-103; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., Adhesive protein interactions with chitosan: Consequences for valve endothelial cell growth on tissue-engineering materials (2003) J Biomed Mater Res Part A, 67 A, pp. 538-547; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) J Biomed Mater Res Part A, 66 A, pp. 247-259; Webb, K., Hlady, V., Tresco, P.A., Relationships among cell attachment, spreading, cytoskeletal organization, and migration rate for anchorage-dependent cells on model surfaces (2000) J Biomed Mater Res, 49, pp. 362-368; Anselme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Lost, A., Hardouin, P., Qualitative and quantitative study of human osteoblast adhesion on materials with various surface roughnesses (2000) J Biomed Mater Res, 49, pp. 155-166; Domard, A., Chitosan interactions (1997) Advances in Chitin Science, pp. 410-420. , Domard A, Roberts GAF, Varum KM, editors. Lyon, France: Jacques André Publisher;
Keywords: Acetylation; Aggregates; alkaline phosphatase; article; Bone Regeneration; bone tissue; Bone tissue engineering; Cell culture; Cell Culture Techniques; Cell filopodia; cell growth; cell proliferation; Cell Shape; cell structure; cell survival; cell viability; chitosan; Collagen; confocal microscopy; controlled study; Cytoskeletal organization; cytoskeleton; Degree of acetylation (DA); enzyme activity; gel permeation chromatography; human; human cell; Humans; infrared spectroscopy; Microstructure; morphology; osteoblast; Osteoblastic cells; Osteoblasts; Phosphatase activity; porosity; Proteins; Scaffold; Scaffolds; Scanning electron microscopy; Substrates; Tissue engineering

Time-lapse analysis of stem-cell divisions in the Arabidopsis thaliana root meristem - Campilho, A.; Garcia, B.; Toorn, H.V.D.; Wijk, H.V.; Campilho, A.; Scheres, B. (Plant JournalPlant J., 2006)
In the Arabidopsis root, asymmetric stem-cell divisions produce daughters that form the different root cell types. Here we report the establishment of a confocal tracking system that allows the analysis of numbers and orientations of cell divisions in root stem cells. The system provides direct evidence that stem cells have lower division rates than cells in the proximal meristem. It also allows tracking of cell division timing, which we have used to analyse the synchronization of root cap divisions. Finally, it gives new insights into lateral root cap formation: epidermal stem-cell daughters can rotate the orientation of the division plane like the stem cell. © 2006 The Authors.
Cited By (since 1996): 33Export Date: 21 November 2012Source: ScopusCODEN: PLJUEdoi: 10.1111/j.1365-313X.2006.02892.xPubMed ID: 17087761Language of Original Document: EnglishCorrespondence Address: Scheres, B.; Department of Molecular Genetics, University of Utrecht, Utrecht, Netherlands; email: b.scheres@bio.uu.nlReferences: Aida, M., Beis, D., Heidstra, R., Willemsen, V., Blilou, I., Galinha, C., Nussaume, L., Scheres, B., The PLETHORA genes mediate patterning of the Arabidopsis root stem cell niche (2004) Cell, 119, pp. 109-120;Baskin, T.I., On the constancy of cell-division rate in the root meristem (2000) Plant Mol. Biol., 43, pp. 545-554; Van Den Berg, C., Willemsen, V., Hendriks, G., Weisbeek, P., Scheres, B., Short-range control of cell differentiation in the Arabidopsis root meristem (1997) Nature, 390, pp. 287-289; Van Den Berg, C., Hage, W., Weisbeek, P., Scheres, B., Laser ablation in Arabidopsis roots: A tool to study cell-to-cell communication (1998) NATO ASI Ser., H104, pp. 237-250; Boisnard-Lorig, C., Colon-Carmona, A., Bauch, M., Hodge, S., Doerner, P., Bancharel, E., Dumas, C., Berger, F., Dynamic analyses of the expression of the HISTONE::YFP fusion protein in Arabidopsis show that syncytial endosperm is divided in mitotic domains (2001) Plant Cell, 13, pp. 495-509; Buvat, R., Structure, evolution et functionnement du méristèm apical de quelques dicotylédones (1952) Ann. Sci. Nat. Bot. Ser., 13, pp. 199-300; Clough, S.J., Bent, A.F., Floral dip: A simplified method for Agrobacterium-mediated transformation of Arabidopsis thaliana (1998) Plant J., 16, pp. 735-743; Clowes, F.A.L., Nucleic acids in root apical meristems of Zea (1956) New Phytol., 55, pp. 29-34; Cutler, S.R., Ehrhardt, D.W., Griffitts, J.S., Somerville, C.R., Random GFP::cDNA fusions enable visualization of subcellular structures in cells of Arabidopsis at a high frequency (2000) Proc. Natl Acad. Sci. USA, 97, pp. 3718-3723; Dolan, L., Janmaat, K., Willemsen, V., Linstead, P., Poethig, S., Roberts, K., Scheres, B., Cellular organization of the Arabidopsis thaliana root (1993) Development, 119, pp. 71-84; Dolan, L., Duckett, C.M., Grierson, C., Linstead, P., Schneider, K., Lawson, E., Dean, C., Roberts, K., Clonal relationships and cell patterning in the root epidermis of Arabidopsis (1994) Development, 120, pp. 2465-2474; Dolznig, H., Grebien, F., Sauer, T., Beug, H., Mullner, E.W., Evidence for a size-sensing mechanism in animal cells (2004) Nat. Cell Biol., 6, pp. 899-905; Furner, I.J., Pumfrey, J.E., Cell fate in the shoot apical meristem of Arabidopsis thaliana (1992) Development, 115, pp. 755-764; Garcia, B., Campilho, A., Scheres, B., Campilho, A., Automatic tracking of Arabidopsis thaliana root meristem in confocal microscopy (2004) ICIAR 2004 LNCS 3212, pp. 166-174. , (Campilho, A. and Kamel, M., eds). New York, Springer Verlag; Irish, V.F., Sussex, I.M., A fate map of the Arabidopsis embryonic shoot apical meristem (1992) Development, 115, pp. 745-753; Jorgensen, P., Nishikawa, J., Breitkreutz, B.J., Tyers, M., Systematic identification of pathways that couple cell growth and division in yeast (2002) Science, 297, pp. 395-400; Nance, J., Priess, J.R., Cell polarity and gastrulation in C. elegans (2002) Development, 129, pp. 387-397; O'Connell, K.F., Leys, C.M., White, J.G., A genetic screen for temperature-sensitive cell-division mutants of Caenorhabditis elegans (1998) Genetics, 149, pp. 1303-1321; Otsu, N., A threshold selection method from gray level histograms (1979) IEEE Trans. Syst. Man. Cybernet., 9, pp. 62-66; Perona, P., Malik, J., Scale space and edge detection using anisotropic diffusion (1990) IEEE Trans. Pattern Anal. Mach. Intel., 12, pp. 629-639; Reddy, G.V., Heisler, M.G., Ehrhardt, D.W., Meyerowitz, E.M., Real-time lineage analysis reveals oriented cell divisions associated with morphogenesis at the shoot apex of Arabidopsis thaliana (2004) Development, 131, pp. 4225-4237; Sabatini, S., Heidstra, R., Wildwater, M., Scheres, B., SCARECROW is involved in positioning the stem cell niche in the Arabidopsis root meristem (2003) Genes Dev., 17, pp. 354-358; Scheres, B., Wolkenfelt, H., Willemsen, V., Terlouw, M., Lawson, E., Dean, C., Weisbeek, P., Embryonic origin of the Arabidopsis primary root and root meristem initials (1994) Development, 120, pp. 2475-2487; Sulston, J.E., Schierenberg, E., White, J.G., Thomson, J.N., The embryonic cell lineage of the nematode Caenorhabditis elegans (1983) Dev. Biol., 100, pp. 64-119; Thomas, C., Devries, P., Hardin, J., White, J., Four-dimensional imaging: Computer visualization of 3D movements in living specimens (1996) Science, 273, pp. 603-607; Watt, F., Hogan, B., Out of Eden: Stem cells and their niches (2000) Science, 287, pp. 1427-1430; Wildwater, M., Campilho, A., Perez-Perez, J.M., Heidstra, R., Blilou, I., Korthout, H., Chatterjee, J., Scheres, B., The RETINOBLASTOMA-RELATED gene regulates stem cell maintenance in Arabidopsis (2005) Cell, 123, pp. 1337-1349
Keywords: Arabidopsis; Arabidopsis thaliana; article; cell cycle; Cell Division; Cells; cytology; Development; Growth; Growth kinetics; Image analysis; meristem; Photoperiod; photoperiodicity; Plant; plant root; Plant roots; Plants; Plants (botany); Real-time; stem cell; Stem cells; Stem-cell daughters; time; Time Factors

Titanium dental implants coated with Bonelike®: Clinical case report - Lobato, J.V.; Sooraj Hussain, N.; Botelho, C.M.; Maurício, A.C.; Lobato, J.M.; Lopes, M.A.; Afonso, A.; Ali, N.; Santos, J.D. (Thin Solid FilmsThin Solid Films, 2006)
The aim of the study was to evaluate the direct bone bonding and osteointegration of the commercial pure (cp Ti) implants coated with Bonelike® synthetic bone graft by plasma spraying. The Bonelike® coated implant was placed in the mandible of a 40-year-old patient and it was removed after a healing period of 3 months with a trephine of 6 mm diameter. The structure of the coating and new bone/implant interface of retrieved samples were evaluated using scanning electron microscopy (SEM) and histological analysis using light microscopy. In vivo microstructure observations of Bonelike® coated retrieved implants showed excellent bone remnants on its surface without any tissue and inflammatory signs observed. The reported Bonelike® coated (cp Ti) implants improved primary stability, which may increase the lifetime of the implant. Bonelike® coated dental implants proved to be highly bioactive with extensive new bone formation and strongly bonded to Bonelike® coating. © 2005 Elsevier B.V. All rights reserved.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: THSFAdoi: 10.1016/j.tsf.2005.12.151Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Murugan, R., Ramakrishna, S., (2005) Compos. Sci. Technol., 65, p. 2385;Boyle, W.J., Simonet, W.S., Lacey, D.L., (2003) Nature, 423, p. 337; Karabuda, C., Ozdemir, O., Tosun, T., Anil, A., Olgac, V., (2001) J. Periodontol., 72, p. 1436; Placko, H.E., Mishra, S., Weimer, J.J., Lucas, L.C., (2000) Int. J. Oral Maxillofac. Implants, 15, p. 355; Jung, Y.C., Han, C.H., Lee, I.S., Kim, H.E., (2001) Int. J. Oral Maxillofac. Implants, 16, p. 809; Kong, Y.M., Kim, D.H., Kim, H.E., Heo, S.J., Koak, J.Y., (2002) J. Biomed. Mater. Res., Part B Appl. Biomater., 63, p. 714; Schutz, R.W., Thomas, D.E., (1987) Metals Handbook. ed. 9, 13, p. 669. , Davis J.R. (Ed), American Society for Metals, Cleveland, OH; Tsui, Y.C., Doyle, C., Clyne, T.W., (1998) Biomaterials, 19, p. 2015; Lavos-Valereto, I.C., Wolynec, S., Deboni, M.C.Z., Konig Jr., B., (2001) J. Biomed. Mater. Res., Part B Appl. Biomater., 58, p. 727; Lacefield, W.R., (1993) An Introduction to Bioceramics, , Hench L.L., and Wilsion J. (Eds), World Scientific, Singapore; Golec, T.S., Krauser, J.T., (1992) Dent. Clin. North Am., 36, p. 39; Block, M.S., Kkent, J.N., (1992) Dent. Clin. North Am., 36, p. 27; Yukna, R.A., (1992) Dent. Clin. North Am., 36, p. 97; Baltag, I., Watanabe, K., Kusakari, H., Taoyuki, N., Miyakawa, O., Kobayashi, M., Ito, N., (2000) J. Biomed. Mater. Res., Part B Appl. Biomater., 53, p. 76; Wheeler, S.L., (1996) Int. J. Oral Maxillofac. Implants, 11, p. 340; Tsui, Y.C., Doyle, C., Clyne, T.W., (1998) Biomaterials, 19, p. 2031; (1981) Science and Medical Applications of Hydroxyapatite, , Conish H., Aoki H., and Sawai K. (Eds), Takyama Press Systems Centre Co., Tokyo; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Santos, J.D., Lakhan, J.J., Monteiro, F.J., (1995) Biomaterials, 16, p. 521; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 20, p. 2085; Lopes, M.A., Silva, R.F., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 21, p. 749; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., (2000) Biomaterials, 21, p. 1165; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Oslen, I., (1998) J. Biomed. Mater. Res., 41, p. 649; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., (2001) J. Mater. Sci., Mater. Med., 12, p. 629; Ferraz, M.P., Monteiro, F.J., Serro, A.P., Saramago, B., Gibson, I.R., Santos, J.D., (2001) Biomaterials, 22, p. 3105; Silva, P.L., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) Surf. Coat. Technol., 102, p. 191; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., (1999) J. Mater. Sci., Mater. Med., 10, p. 567; Lobato, J.V., Sooraj Hussain, N., Sousa, R.C., Maurício, A.C., Santos, J.D., (2005) Br. J. Oral Maxillofac. Surg., , (Communicated); Bränemark, P.I., Svensson, B., van Steenberghe, D., (1995) Clin. Oral Implants Res., 6 (4), p. 227; Strnad, Z., Strand, J., Povysil, C., Urban, K.K., (2000) Int. J. Oral Maxillofac. Implants, 15, p. 483; Ross, M.H., Romrell, L.J., Kaye, G.I., (1995) Histology, a Text and Atlas. ed. 3, , Williams & Wilkins, New York
Keywords: Bone; Bone Regeneration; Bone/implant interface; Bonelike® coatings; Clinical applications; Dental Implants; Dental prostheses; Hip prostheses; Medical applications; Optical microscopy; Plasma spraying

Adsorption isotherm of sodium ampicillin onto dense and porous hydroxyapatite - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2005)
The adsorption behaviour of sodium ampicillin to dense and porous hydroxyapatite as been extensively studied through the obtention of an adsorption isotherm. This isotherm was produced at body temperature, and a wide range of antibiotic solutions were used. The adsorption behaviour was measured by UV spectroscopy. The shape of the isotherm for the two forms of the material,dense and porous, indicates that the adsorption behaviour of the antibiotic seems to be different, however this is due to the adsorption taking place within the pores of the porous material, thus showing a larger amount of antibiotic adsorbed.
Keywords: Adsorption; Adsorption behavior; Adsorption isotherms; ampicillin; Antibiotics; hydroxyapatite; Porous hydroxyapatite; Porous materials; Sodium ampicillin; Sodium compounds; Ultraviolet spectroscopy

Assessment of the potential of Bonelike® graft for bone regeneration by using an animal model - Lobato, J.V.; Hussein, N.S.; Botelho, C.M.; Rodrigues, J.M.; Luís, A.L.; Maurício, A.C.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2005)
Bonelike® graft that mimics the inorganic composition of bone tissue has been developed and characterized over the last decade. To evaluate the osteoconductivity of Bonelike® two granule size ranges, one ranging from 150-250μm and the other from 250-500μm were implanted in the femurs of New Zealand White rabbits, aiming at being clinically used in different medical applications, such as dentistry and orthopaedics. In order to facilitate the medical application of the Bonelike® graft the use of a commercially available polymeric vehicle was also analyzed. Radiological examination, histological studies and scanning electron microscopy (SEM) analyses revealed that the surface of Bonelike® granules was almost completely surrounded by new bone formation after 12 weeks of implantation, which proves its highly osteoconductive behaviour.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Lobato, J.V.; ICBAS-Instituto de Ciências Biomédicas de Abel Salazar, Universidade do Porto, Largo Professor Abel Salazar 2, PT-4099-003 Porto, Portugal; email: jvlobato@netcabo.ptReferences: Santos, J.D., Hastings, G.W., Knowles, J.C., Sintered Hydroxyapatite Compositions and Method for the Preparation Thereof European Patent WO 0068164Lopes, M.A., Santos, J.D., Monteiro, F.J., Push-out Testing and Histological Evaluation of Glass Reinforced Hydroxyapatite Composites Implanted in the Tibia of Rabbits (2001) J.Biomed Mater Res, 54, pp. 463-469;Lopes, M.A., Santos, J.D., Glass Reinforced Hydroxyapatite Composites; Secondary Phases Proportions and Densification Effects on Biaxial Bending Strength (1999) J.Biomed Mater Res, 48, pp. 734-740; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass Reinforced Hydroxyapatite Composites: Fracture Tougfiness and Hardness Dependence on Microstructural Characteristics (1999) Biomaterials, 2, pp. 2085-2090
Keywords: animal model; Animal models; Animals; Biomaterials; Biomedical engineering; Biomimetic materials; Bone; bone tissue; Bonelike graft; Bonelike® graft; Granular materials; In vivo studies; Scanning electron microscopy

Biological behaviour of Bonelike® graft implanted in the tibia of humans - Gutierres, M.; Hussain, N.S.; Afonso, A.; Almeida, L.; Cabral, T.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2005)
This paper reports the ability of Bonelike® to regenerate bone defected areas when implanted in the tibia of 3 patients (average age of 59 years) during a high tibial osteotomy (HTO) to treat medial compartment osteoarthritis of the knee. Bonelike® is a synthetic bone graft designed to mimic the inorganic composition of bone using a patent process that consists of liquid sintering hydroxyapatite in the presence of CaO-P 2O 5 based glass. The preliminary clinical evaluation performed showed that an intimate contact between new formed bone and Bonelike® was established (67±10%), with no fibrous interface. Therefore, Bonelike® is a single-handedly viable osteoconductive synthetic grafting material as it has been demonstrated from the profiles of radiological, histological and scanning electron microscopy analyses for the six months implantation period.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Gutierres, M.; Faculdade de Medicina da Universidade do Porto, Hospital de São João, Largo Hernâni Monteiro, 4200 Porto, Portugal; email: m.gutierres@clix.ptReferences: Bauer, T.W., Muschler, G.F., Bone Graft Materials. An Overview of the Basic Science (2000) Clin orthop Rel. Res, 371, pp. 10-27;Perry, C.R., Bone Repair Techniques, Bone Graft and Bone Graft Substitutes (1999) Clin Orthop Rel Res, 360, pp. 71-86; Ilan, D.I., Ladd, A.L., Bone graft substitutes (2003) Operative Tech. in plastic and Reconstructive Surgery, 9 (4), pp. 151-160; Santos, J.D., Hastings, G.W., Knowles, J.C., Sintered Hydroxyapatite Compositions and Method for the Preparation Thereof European Patent WO 0068164Lopes, M.A., Glass reinforced hydroxyapatite composites: Structural, Physicochemical characterisation and Biological performance (1999), PhD thesis, FEUP, University of Porto, PortugalCoventry, M.B., Osteotomy of the upper portion of the tibia for degenerative arthritis of the knee: A preliminary report (1965) J. Bone Joint Surg.Am, 47, p. 984; Lopes, M.A., Santos, J.D., (2001) J.Biomed Mat Res, 54, pp. 463-469
Keywords: Biological behavior; Bone; Bonelike® graft; Clinical trials; histology; hydroxyapatite; Implants (surgical); Radiology; Scanning electron microscopy; Surgery; Synthetic grafting material

Biological evaluation of calcium alginate microspheres as a vehicle for the localized delivery of a therapeutic enzyme - Barrias, C.C.; Lamghari, M.; Granja, P.L.; Sá Miranda, M.C.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2005)
Gaucher disease (GD) is caused by the decreased activity and/or stability of the lysosomal enzyme glucocerebrosidase (GCR). The available treatment consists in the intravenous administration of exogenous GCR, and is effective in reverting most of the symptoms. However, in terms of bone pathology, which is among the most disabling manifestations, a slow and incomplete response is observed, indicating that adjuvant therapies are necessary to consistently restore GCR activity in bone and accelerate regeneration. In this study, calcium alginate microspheres were analyzed as a vehicle for localized GCR delivery to bone. Results demonstrated that the entrapped enzyme retained full activity and exhibited a broader pH-dependent activity profile, compared to that of free-GCR, with improved stability at physiological pH. GCR release profile was established, and it was demonstrated that GCR could be released in a sustained manner. The biological behavior of the system was evaluated by analyzing the uptake of released GCR by GCR-deficient cells from GD patients, using different techniques: GCR activity measurements, radiolabeling, and cellulose acetate electrophoresis. Results demonstrated that GCR was internalized by cells significantly enhancing the residual enzymatic activity. To achieve an activity reconstitution level comparable to that obtained using free-GCR, only half of the dose was required with entrapped-GCR. © 2005 Wiley Periodicals, Inc.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30348PubMed ID: 16028235Language of Original Document: EnglishCorrespondence Address: Barrias, C.C.; Instituto de Engenharia Biomédica (INEB), Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: ccbarrias@ineb.up.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; calcium alginate, 9005-35-0; glucosylceramidase, 37228-64-1; iodine 125, 14158-31-7, 22822-81-7; Alginates; alginic acid, 9005-32-7; Drug Carriers; Enzymes, Immobilized; Glucosylceramidase, EC 3.2.1.45; Glucuronic Acid, 576-37-4; Hexuronic AcidsManufacturers: GenzymeReferences: Grabowski, G.A., Leslie, N., Wenstrup, R., Enzyme therapy for Gaucher disease: The first 5 years (1998) Blood Rev, 12, pp. 115-133;Zhao, H., Grabowski, G.A., Gaucher disease: Perspectives on a prototype lysosomal disease (2002) Cell Mol Life Sci, 59, pp. 694-707; Friedman, B., Vaddi, K., Preston, C., Mahon, E., Cataldo, J.R., McPherson, J.M., A comparison of the pharmacological properties of carbohydrate remodeled recombinant and placental-derived beta-glucocerebrosidase: Implications for clinical efficacy in treatment of Gaucher disease (1999) Blood, 93, pp. 2807-2816; Rasmussen, J., Barsomian, G., Bergh, M., Enzymatically active recombinant glucocerebrosidase. U.S. patent 6451600. 17 September 2002Elstein, D., Itzchaki, M., Mankin, H.J., Skeletal involvement in Gaucher's disease (1997) Baillieres Clin Haematol, 10, pp. 793-816; Wenstrup, R.J., Roca-Espiau, M., Weinreb, N.J., Bembi, B., Skeletal aspects of Gaucher disease: A review (2002) Br J Radiol, 75 (SUPPL. 1), pp. A2-A12; Mistry, P.K., Wraight, E.P., Cox, T.M., Therapeutic delivery of proteins to macrophages: Implications for treatment of Gaucher's disease (1996) Lancet, 348, pp. 1555-1559; Gregoriadis, G., Neerunjun, D., Meade, T.W., Goolamali, S.K., Weereratne, H., Bull, G., Experiences after long-term treatment of a type I Gaucher disease patient with liposome-entrapped glucocerebroside: Beta-glucosidase (1980) Birth Defects Orig Artic Ser, 16, pp. 383-392; Dale, G.L., Kuhl, W., Beutler, E., Incorporation of glucocerebrosidase into Gaucher's disease monocytes in vitro (1979) Proc Natl Acad Sci USA, 76, pp. 473-475; Beutler, E., Dale, G.L., Guinto, D.E., Kuhl, W., Enzyme replacement therapy in Gaucher's disease: Preliminary clinical trial of a new enzyme preparation (1977) Proc Natl Acad Sci USA, 74, pp. 4620-4623; Belchetz, P.E., Crawley, J.C., Braidman, I.P., Gregoriadis, G., Treatment of Gaucher's disease with liposome-entrapped glucocerebroside: Beta-glucosidase (1977) Lancet, 2, pp. 116-117; Korablyov, V., Zimran, A., Barenholz, Y., Cerebroside-beta-glucosidase encapsulation in liposomes for Gaucher's disease treatment revisited (1999) Pharm Res, 16, pp. 466-469; Busto, M.D., Ortega, N., Perez-Mateos, M., Effect of immobilization on the stability of bacterial and fungal beta-glucosidase (1997) Process Biochem, 32, pp. 441-449; Dashevsky, A., Protein loss by the microencapsulation of an enzyme (lactase) in alginate beads (1998) Int J Pharm, 161, pp. 1-5; Blandino, A., Macias, M., Cantero, D., Immobilization of glucose oxidase within calcium alginate gel capsules (2001) Process Biochem, 36, pp. 601-606; Kokufuta, E., Shimizu, N., Tanaka, H., Nakamura, I., Use of polyelectrolyte complex-stabilised calcium alginate gel for entrapment of beta-amylase (1988) Biotechnol Bioeng, 33, pp. 756-759; Edelman, E.R., Mathiowitz, E., Langer, R., Klagsbrun, M., Controlled and modulated release of basic fibroblast growth factor (1991) Biomaterials, 12, pp. 619-626; Peters, M.C., Isenberg, B.C., Rowley, J.A., Mooney, D.J., Release from alginate enhances the biological activity of vascular endothelial growth factor (1998) J Biomater Sci Polym Ed, 9, pp. 1267-1278; Alsberg, E., Anderson, K.W., Albeiruti, A., Franceschi, R.T., Mooney, D.J., Cell-interactive alginate hydrogels for bone tissue engineering (2001) J Dent Res, 80, pp. 2025-2029; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20, pp. 45-53; Gagne, T.A., Chappell-Afonso, K., Johnson, J.L., McPherson, J.M., Oldham, C.A., Tubo, R.A., Vaccaro, C., Vasios, G.W., Enhanced proliferation and differentiation of human articular chondrocytes when seeded at low cell densities in alginate in vitro (2000) J Orthop Res, 18, pp. 882-890; (1993) Iodine-125. A Guide to Radioiodination Techniques: Amersham Life Science, , Amersham Place, Little Chalfont, Bucks: Amersham International pic; 64 pp; Sa Miranda, M.C., Aerts, J.M., Pinto, R., Fontes, A., De Lacerda, L.W., Van Weely, S., Barranger, J., Tager, J.M., Activity of glucocerebrosidase in extracts of different cell types from type 1 Gaucher disease patients (1990) Clin Genet, 38, pp. 218-227; Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., Measurement of protein using bicinchoninic acid (1985) Anal Biochem, 150, pp. 76-85; Sa Miranda, M.C., Aerts, J.M., Pinto, R.A., Magalhaes, J.A., Barranger, J.A., Tager, J.M., Schram, A.W., Heterogeneity in human acid beta-glucosidase revealed by cellulose-acetate electrophoresis (1988) Biochim Biophys Acta, 965, pp. 163-168; Smidsrod, O., Draget, K.I., Chemistry and physical properties of alginates (1996) Carbohyd Eur, 14, pp. 6-13; Gaserod, O., Sannes, A., Skjak-Braek, G., Microcapsules of alginate-chitosan. II. A study of capsule stability and permeability (1999) Biomaterials, 20, pp. 773-783; Aslani, P., Kennedy, R.A., Studies on diffusion in alginate gels. I. Effect of cross-linking with calcium or zinc ions on diffusion of acetaminophen (1996) J Control Release, 42, pp. 75-82
Keywords: Alginates; alginic acid; article; Bone; bone disease; Bone Regeneration; Calcium alginate; Calcium Compounds; catalysis; Cell culture; Cells, Cultured; controlled study; Drug Carriers; drug delivery system; enzyme activity; enzyme assay; enzyme replacement; Enzymes; Enzymes, Immobilized; fibroblast culture; Fibroblasts; Gaucher disease; Gaucher disease (GD); Glucocerebrosidase (GCR); Glucosylceramidase; Glucuronic Acid; Hexuronic Acids; human; human cell; Humans; iodine 125; Localized delivery; lysosome enzyme; lysosome storage disease; microsphere; Microspheres; Pathology; pH effects; physiology; recombinant enzyme; Therapeutic enzyme

Bone substitutes: General concepts and "state of the art" - Gutierres, M.; Ascensão Lopes, M.; Sooraj Hussain, N.; Trigo Cabral, A.; Almeida, L.; Domingos Santos, J. (Substitutos ósseos: Conceitos gerais e estado actualArquivos de MedicinaArq. Med., 2005)
Bone grafts are nowadays the subject of extensive research worldwide, aimed at overcoming limitations associated with the use of autografts or bone banks to fill bone defects. Additionally, the use of osteogenic substances opens new perspectives in the treatment of fractures, pseudarthroses and vertebral arthrodeses. Due to the large amount of information available in the area of bone grafts, this paper aims not only to revise general concepts but also to summarize what has been published recently in the area of bone substitutes for bone regeneration. ©ArquiMed, 2006.
Keywords: Autografts; biomaterial; bone defect; bone demineralization; bone development; Bone graft; Bone growth factors; Bone morphogenetic protein; bone prosthesis; calcium phosphate; calcium sulfate; cortical bone; fibroblast growth factor; fracture; health care facility; health status; human; hydroxyapatite; platelet derived growth factor; pseudarthrosis; publication; review; somatomedin C derivative; spondylarthritis; transforming growth factor

Bonelike®/PLGA hybrid materials for bone regeneration: Preparation route and physicochemical characterisation - Oliveira, J.M.; Miyazaki, T.; Lopes, M.A.; Ohtsuki, C.; Santos, J.D. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2005)
Bonelike®/PLGA hybrid materials have been developed using γ-MPS as silane-coupling agent between the inorganic and organic phases for controlled drug delivery applications. Silanization showed to be more effective when cyclohexane was used as a non-polar solvent (nP method) due to a chemical interaction between Bonelike®, and the silane film, while by using a 95/5 (V/V) methanol/water as a polar solvent (P method), a much thinner film was achieved. Functional groups of PLGA, such as the carbonyl group (C=O), were identified using Raman and FTIR-ATR analysis and therefore these groups may be used to link therapeutic molecules. These novel hybrid materials prepared by combining silanization and post-hybridisation processes are expected to find use in medical applications of bone regeneration and as drug delivery carrier for therapeutic molecules. © 2005 Springer Science + Business Media, Inc.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-005-6687-yLanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB - Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; lactic acid, 113-21-3, 50-21-5; polyglycolic acid, 26124-68-5; cyclohexane, 110-82-7; methanol, 67-56-1; polyglactin, 26780-50-7, 34346-01-5; silane, 7803-62-5; water, 7732-18-5; Durapatite, 1306-06-5; Lactic Acid, 50-21-5; Polyglycolic Acid, 26009-03-0; polylactic acid-polyglycolic acid copolymer; Polymers; SilanesTradenames: Bonelike, AldrichManufacturers: AldrichReferences: Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , JAAS;Glimcher, M.J., (1976) Handbook of Physiology, Endocrinology, , edited by R. O. Greep and E. B. Astwood (American Physiological Society, Washington D.C.); Shors, E.C., Holmes, R.E., (1993) An Introduction to Bioceramics, p. 181. , edited by L. L. Hench and J. Wilson (World Scientific, Hong-Kong); Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 48, p. 734; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 20, p. 2085; Lopes, M.A., Silva, R.F., Monteiro, F.J., Santos, J.D., (2000) Biomaterials, 21, p. 749; Lopes, M.A., Knowles, J.C., Santos, J.D., (2000) Biomaterials, 21, p. 1905; Jha, L.J., Santos, J.D., Knowles, J.C., (1996) J. Biomed. Mater. Res., 31, p. 481; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., (2001) J. Mater. Sci.: Mater. Med., 12, p. 629; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., (2000) Biomaterials, 21, p. 1165; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463; Wang, M., Deb, S., Bonfield, W., (2000) Mater. Lett., 44, p. 119; George, I., Viel, P., Bureau, C., Suski, J., Lécayon, G., (1996) Surf. Interf. Anal., 24, p. 774; Liu, Q., De Wijn, J.R., De Groot, K., Van Blitterwijk, C.A., (1998) Biomaterials, 19, p. 1067; Ara, M., Watanabe, M., Imai, Y., (2002) Biomaterials, 23, p. 2479; Agrawal, C.M., Ray, R.B., (2001) J. Biomed. Mater. Res., 55, p. 141; Arnold, U., Lindenhayn, K., Perka, C., (2002) Biomaterials, 23, p. 2303; Rizzi, S.C., Heath, D.J., Coombes, A.G.A., Bock, N., Textor, M., Downes, S., (2001) J. Biomed. Mater. Res., 55, p. 475; Simon Jr., C.G., Khatri, C.A., Wight, S.A., Wang, F.W., (2002) J. Orthop. Res., 20, p. 473; Mikos, A.G., Temenoff, J.S., (2000) EJB Electr. J. Biotechn., 3 (2); Laurencin, C.T., Attawia, M.A., Lu, L.Q., Borden, M.D., Lu, H.H., Gorum, W.J., Lieberman, J.R., (2001) Biomaterials, 22, p. 1271; Takenaga, M., Yamaguchi, Y., Kitagawa, A., Ogawa, Y., Mizushima, Y., Igarashi, R., (2002) J. Contr. Rel., 79, p. 81; Dupraz, A.M.P., De Wijn, J.R., Van De Meer, S.A.T., De Groot, K., (1996) J. Biomed. Mater. Res., 30, p. 231; Sheldon, R.P., (1982) Appl. Sci. Publ., 1, p. 1; Zhu, P.X., Ishikawa, M., Seo, W.S., Hozumi, A., Yokogawa, Y., Koumoto, K., (2002) J. Biomed. Mater. Res., 59, p. 294; Hooshmand, T., Van Noort, R., Keshvad, A., (2002) Dent. Mater., 18, p. 179; Venhoven, B.A.M., De Gee, A.J., Werner, A., Davidson, C.L., (1994) Biomaterials, 15, p. 1152; Yerby, S.A., Paal, A.F., Young, P.M., Beaupré, G.S., Ohashi, K.L., Goodman, S.B., (2000) J. Biomed. Mater. Res., 49, p. 127; Wang, M., Bonfield, W., (2001) Biomaterials, 22, p. 1311; Santos, C., Luklinska, Z.B., Clarke, R.L., Davy, K.W.M., (2001) J. Mater. Sci.: Mat. Med., 12, p. 565; Santos, J.D., Knowles, J.C., Hastings, G.W., in "Sintered Hydroxyapatite Compositions and Method for the Preparation Thereof," European Patent No. WO0068164 (2000)Afonso, A., Santos, J.D., Vasconcelos, M., Branco, R., Cavalheiro, J., (1996) J. Mater. Sci.: Mater. Med., 7, p. 507; Hoffman, R., Westheim, J.G.F., Pouwel, I., Fransen, T., Gellings, P.J., (1996) Surf. Interf. Anal., 24, p. 1; Rider, A.N., Arnott, D.R., (1996) Surf. Interf. Anal., 24, p. 583; Eufinger, S., Van Ooij, W.J., Conners, K.D., (1996) Surf. Interf. Anal., 24, p. 841
Keywords: analytic method; article; Biological materials; Bone; Bone Regeneration; carbonyl derivative; chemical bond; chemical interaction; chemical reaction; Chemical reactions; chemistry; Chemistry, Physical; cyclohexane; Drug delivery; drug delivery system; Drug therapy; Durapatite; film; Fourier transform infrared spectroscopy; Hybrid materials; hybridization; hydroxyapatite; infrared spectroscopy; Lactic Acid; methanol; methodology; Microscopy, Electron, Scanning; Molecules; physical chemistry; polyglactin; polyglycolic acid; polylactic acid polyglycolic acid copolymer; polylactic acid-polyglycolic acid copolymer; polymer; Polymers; priority journal; Raman spectrometry; Raman spectroscopy; reaction analysis; Scanning electron microscopy; silane; silane derivative; Silanes; Silanization; solvent effect; Solvents; Spectroscopy, Fourier Transform Infrared; Spectrum Analysis, Raman; synthesis; Water; X ray; X-Rays

Development of a system to adsorb drugs onto calcium phosphate materials - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2005)
Several studies were carried out in order to reduce the systemic use of antibiotics due to the high concentration required to provide the minimum inhibitory concentration (MIC) at infected sites. The aim of this study was to develop a system of drug adsorption onto commercial hydroxyapatite (HA, Ca 10(PO 4) 6(OH) 2) and glass reinforced hydroxyapatite (GR-HA) granules. The drug will then be released for the local treatment of periodontitis. The antibiotics used in this study were metronidazole, a specific antibiotic indicated for the systemic treatment of periodontitis, and ampicillin, a wide spectrum antibiotic. UV spectroscopy was used to measure the amount of drug adsorbed onto HA and GR-HA granules. Results showed that metronidazole was unable to adsorb on the material's surface, as opposed to ampicillin which adsorbed both onto HA and GR-HA. Preliminary release kinetics studies were carried out using a flow through dissolution system. Results are discussed in terms of the influence of the different surface characteristics of the materials on the adsorption processes. © 2005 Springer Science + Business Media, Inc.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-005-2535-3PubMed ID: 15965596Language of Original Document: EnglishCorrespondence Address: Queiroz, A.C.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180, Porto, Portugal; email: aqueiroz@ineb.up.ptChemicals/CAS: ampicillin, 69-52-3, 69-53-4, 7177-48-2, 74083-13-9, 94586-58-0; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; metronidazole, 39322-38-8, 443-48-1; Ampicillin, 69-53-4; Anti-Infective Agents; calcium phosphate, 10103-46-5; Calcium Phosphates; Coated Materials, Biocompatible; Delayed-Action Preparations; Drug Carriers; Metronidazole, 443-48-1References: Seymour, R.A., Heasman, P.A., Macgregor, I.D.M., (1992) Drugs, Diseases, and the Periodontium, 1. , edited by R. A. Seymour and P. A. Heasman Oxford University Press, Oxford;Carnevale, R.A., Greco, G.W., Bullard, C.M., Hanker, J.S., (1987) Biomedical Materials and Devices, p. 247. , edited by J. S. Hanker and B. L. Giammara Materials Research Society, Pittsburgh; Friedman, M., Steinberg, D., (1990) Pharm. Res., 7, p. 313; Hagiwara, S., Takamatsu, N., Tominaga, Y., Umeda, M., (1998) J. Period., 69, p. 62; Wright, T.L., Ellen, R.P., Lacroix, J.M., Sinnadurai, S., Mittelman, M.W., (1997) J. Period. Res., 32, p. 473; Golomb, G., Friedman, M., Soskolne, A., Stabholz, A., Sela, M.N., (1984) J. Dent. Res., 63, p. 1149; Goodson, J.M., Hogan, P.E., Dunham, S.L., (1984) J. Period., 55, p. 81; Somayaji, B.V., Jariwala, U., Jayachandran, P., Vidyalakshim, K., Dudhani, R.V., (1998) J. Period., 69, p. 409; Stoltze, K., (1992) J. Clin. Period., 19, p. 698; Goodson, J.M., Holborow, D., Dunn, R.L., Hogan, P., Dunham, S., (1983) J. Period., 54, p. 575; Yu, D., Wong, J., Matsuda, Y., Fox, J.L., Higuchi, W.I., Otsuka, M., (1992) J. Pharm. Sci., 81, p. 529; Nishihara, K., (1993) Clin. Mater., 12, p. 159; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mat. Res., 45, p. 376; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mat. Res., 47, p. 603; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mat. Res., 54, p. 463; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Gibson, I.R., Knowles, J.C., (2001) Biomaterials, 22, p. 1393; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Knowles, J.C., Santos, J.D., Hastings, G.W., World Patent, WO0068164 (1994)Myers, H.M., Tochon-Danguy, H.J., Baud, C.A., (1983) Calcif. Tissue Int., 35, p. 745; Ratier, A., Gibson, I.R., Best, S.M., Freche, M., Lacout, J.L., Rodrigues, F., (2001) Biomaterials, 22, p. 897; Ando, D.J., (1996) Ultraviolet and Visible Spectroscopy, p. 16. , John Wiley & Sons, West Sussex
Keywords: Adsorption; ampicillin; Anti-Infective Agents; Antibiotics; article; Calcium Compounds; calcium phosphate; Calcium phosphates; Coated Materials, Biocompatible; concentration response; Delayed-Action Preparations; Diffusion; Dissolution; drug absorption; drug adsorption; Drug Carriers; Drug release; drug stability; glass; Glass reinforced hydroxyapatie (GR-HA); human; Humans; hydroxyapatite; Kinetics; Material's surface; Materials science; materials testing; metronidazole; minimum inhibitory concentration; Minimum inhibitory concentration (MIC); periodontitis; priority journal; Reaction kinetics; reduction; surface property; Ultraviolet spectroscopy

Feature extraction for classification of thin-layer chromatography images - Sousa, A.V.; Mendonça, A.M.; Campilho, A.; Aguiar, R.; Sá Miranda, C. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2005)
Thin-Layer Chromatography images are used to detect and identify the presence of specific oligosaccharides, expressed by the existence, at different positions, of bands in the gel image. ID gaussian deconvolution, commonly used for band detection, does not produce good results due to the large curvature observed in the bands. To overcome this uncertainty on the band position, we propose a novel feature extraction methodology that allows an accurate modeling of curved bands. The features are used to classify the data into two different classes, to differentiate normal from pathologic cases. The paper presents the developed methodology together with the analysis and discussion of the results. © Springer-Verlag Berlin Heidelberg 2005.
Conference code: 67124Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1007/11559573_118Language of Original Document: EnglishCorrespondence Address: Sousa, A.V.; Instituto de Engenharia Biomédica, Rua Roberto Frias, 4200-465 Porto, Portugal; email: ats@isep.ipp.ptReferences: Bajla, I., Holländer, I., Burg, K., Improvement of electrophoretic gel image analysis (2001) M. S.R, 1 (1);Ye, X., Suen, C., Cheriet, M., Wang, E., A recent development in image analysis of electrophoresis gels (1999) Vision Interface 99, , Canada; Shadle, S., Allen, D., Guo, H., Pogozelski, W., Bashkin, J., Tullius, T., Quantitative analysis of electrophoresis data: Novel curve fitting methodology and its application to the determination of aprotein-DNA binding constant (1997) Nucleic Acids Research, 25 (4); Sousa, A., Aguiar, R., Mendonça, A.M., Campilho, A., Automatic lane and band detection in images of thin layer chromatography (2004) Springer Lecture Notes on Computer Science, LNCS, 3212, pp. 372-380; Heijden, F., Duin, R., Ridder, D., Tax, D., (2004) Classification, Parameter Estimation and State Estimation, , John Wiley and Sons, England; Sewell, A., (1991) Urinary Oligosaccharides. Techniques in Diagnostic Human Biochemical Genetics, pp. 219-231. , Willey-Liss, Inc; Thomas, G., Disorders of Glycoprotein Degradation. α-Mahnosidosis, β-Mannosidosis, Fucosidosis and Sialidosis. Disorders of Glycoprotein Degradation, , Chap. 140; Durant, G., Seta, N., Protein glycosylation and diseases: Blood and urinary oligosaccharides as markers for diagnosis and therapeutic monitoring (2000) Clinical Chemistry, 46 (6), pp. 795-805; Marques De Sá, J., (2003) Applied Statistics Using SPSS, STATISTICA and MATLAD, , Springer Verlag
Keywords: Edge detection; Feature extraction; Image analysis; Image segmentation; Oligosaccharides; Thin layer chromatography; Thin-Layer Chromatography images

In situ thermal and structural characterization of bioactive calcium phosphate glass ceramics containing TiO 2 and MgO oxides: High temperature - XRD studies - Dias, A.G.; Skakle, J.M.S.; Gibson, I.R.; Lopes, M.A.; Santos, J.D. (Journal of Non-Crystalline SolidsJ Non Cryst Solids, 2005)
This study aims to develop glass ceramics in the calcium phosphate system that exhibit suitable properties to be used for biomedical applications. Calcium phosphate glasses with the incorporation of small additions of MgO and TiO 2 oxides were prepared in the pyro-and orthophosphate regions. The glass ceramics were prepared by a controlled powder sintering process through heat-treatment at different temperatures, as defined by results from differential thermal analysis (DTA). The composition of the crystalline phases precipitated in the glassy matrix as a result of heat treatments at different temperatures, ranging from 681 to 725 °C, was determined from X-ray diffraction data. The sequence of phase crystallization in the mother glass was also studied in situ using high temperature X-ray diffraction (HT-XRD) analysis. Results showed that the first phases that precipitated in the glass matrix were α- and β-Ca 2P 2O 7 at 620 °C. A small amount of CaTi 4(PO 4) 6 appeared at 630 °C. At 650 °C the three phases α-Ca 2P 2O 7, β-Ca 2P 2O 7 and CaTi 4(PO 4) 6 were clearly presented with a small amount of TiP 2O 7 and finally at 660 °C all four phases were observed. Glass ceramics were also characterized using Raman and X-ray photoelectron spectroscopy. This study demonstrates that, by altering the heat treatment cycle, it is possible to prepare glass ceramics in the calcium phosphate system that contains different bioactive and biocompatible phases. © 2005 Published by Elsevier B.V.
Cited By (since 1996): 24Export Date: 21 November 2012Source: ScopusCODEN: JNCSBdoi: 10.1016/j.jnoncrysol.2005.01.060Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Depto. De Engenharia Metalurgica E., Faculdade De Engenharia Da Univ. D., Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Franks, K., Abrahams, I., Georgiou, G., Knowles, J.C., (2001) Biomaterials, 22, p. 497;Rizkalla, A.S., Jones, D.W., Clarke, D.B., Hall, G.C., (1996) J. Biomed. Mater. Res., 32, p. 119; Navarro, M., Clément, J., Ginebra, M.P., Avila, G., Martínez, S., Planell, J.A., (2002) 17th European Society for Biomaterials Conference Proceedings, , Barcelona; Zhang, Y., Lopes, M.A., Santos, J.D., (2000) Bioceramics, 13, p. 643; Navarro, M., Clément, J., Ginebra, M.P., Martínez, S., Avila, G., Planell, J.A., (2002) Key Eng. Mater., 218-220, p. 275; Ohtsuki, C., Osaka, A., Kokubo, T., (1994) Bioceramics, 7, p. 73; Suzuki, T., Toriyama, M., Hosono, H., Abe, Y., (1991) J. Ferment. Bioeng., 72, p. 384; Abe, Y., Hosono, H., Hosoe, M., (1987) Phosphorus Sulfur, 30, p. 337; Schneider, K., Heimann, R.B., Berger, G., (2001) Werkstofftech., 32, p. 166; Lin, F.H., Lin, C.C., Lu, C.M., (1995) Biomaterials, 16, p. 793; Lin, C.C., Liao, C.J., Sun, J.S., (1996) Biomaterials, 17, p. 1133; Dias, A.G., Tsuru, K., Hayakawa, S., Lopes, M.A., Santos, J.D., Osaka, A., (2004) Glass Technol., 45, p. 78; Bish, D.L., Howard, S.A., (1988) J. Appl. Cryst., 21, p. 86; De Fátima Gimenez, I., Mazali, I.O., Alves, O.L., (2001) J. Phys. Chem. Solids, 62, p. 1251; Krimi, S., Eljazouli, A., Rabardel, L., Couzi, M., Mansouri, I., Leflem, G., (1993) J. Solid State Chem., 102, p. 400; Barj, M., Lucazeau, G., Delmas, C., (1992) J. Solid State Chem., 100, p. 141; NIST Standard Reference Database; Shih, P.Y., Yung, S.W., Chin, T.S., (1998) J. Non-Cryst. Solids, 224, p. 143; Reaney, I.M., James, P.F., Lee, W.E., (1996) J. Am. Ceram. Soc., 79, p. 1934; Ryu, H.-S., Youn, H.-J., Chang, B.-S., Lee, C.-K., Chung, S.-S., (2002) Biomaterials, 23, p. 909; Kitsugi, T., Yamamuro, T., Nakamura, T., Oka, M., (1995) Biomaterials, 16, p. 1101; Dias, A.G., Costa, M.A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2004) Key Eng. Mater., 254-256, p. 825; Bian, J.J., Kim, D.W., Hong, K.S., (2003) J. Eur. Ceram. Soc., 23 (14), p. 2589; Clarck, T.J., Reed, J.S., (1986) J. Am. Ceram. Soc., 69, p. 837; Siligardi, C., D'Arrigo, M.C., Leonelli, C., (2000) Am. Ceram. Soc. Bull., p. 88; Chowdari, V.R., Subba Rao, G.V., Lee, G.Y.H., (2000) Solid State Ionics, 136-137, p. 1067
Keywords: Biocompatibility; Calcium Compounds; Calcium phosphate systems; Cavity fillers; Computer software; Crystallinity; Differential thermal analysis; Fourier transform infrared spectroscopy; Glass ceramics; Magnesia; Phase analysis; Raman spectroscopy; Titanium dioxide; X ray diffraction analysis; X ray photoelectron spectroscopy

In vitro analysis of protein adhesion to phase pure hydroxyapatite and silicon substituted hydroxyapatite - Botelho, C.M.; Brooks, R.A.; Kawai, T.; Ogata, S.; Ohtsuki, C.; Best, S.M.; Lopes, M.A.; Santos, J.D.; Rushton, N.; Bonfield, W. (Key Engineering MaterialsKey Eng Mat, 2005)
The adhesion of bovine collagen type I, bovine serum albumin, bovine IgG, 1 % and 10 % (v/v) human serum to hydroxyapatite (HA), silicon-substituted hydroxyapatite (Si-HA) and tissue culture plastic were studied. The materials were incubated at 37°C for 30 minutes, after which the protein solution was removed and analyzed. The adsorbed protein was evaluated by electrophoresis and immunoassay after extraction from the materials. The degree of adhesion was higher for collagen, followed by IgG and albumin on all materials. However there was no difference in the amount of collagen adsorbed onto the surface of each material and this was also the finding with albumin and IgG. These results suggest that the increased bioactivity seen with Si-HA is not due to the degree of protein adhesion, but may possibly be due to changes in the conformation of the bound proteins.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Botelho, C.M.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: ccunha@fe.up.ptReferences: Patel et al, J. of Mat. Sci.: Mat. in Med., 13 (2002) p. 1199Gibson, I.R., (1999) Bioceramics, 12, p. 191;Botelho, C.M., in Key (2003) Engineering Materials, 254-256, pp. 841-844; Porter, (2004) Biomaterials, 5, pp. 3303-3314; Takami et al, in J. Biomed Mater. Res., 40, (1998), p. 24-30Kandori, (2004) in J. Colloid and Interface Science, 273, pp. 406-413; Vermeer, (2001) Biochimicaet Biophysica Acta, 1526, pp. 61-69; Kikuchi, (2001) Biomaterials, 22, pp. 1705-1711; Jha, L.J., Worldwide patent, PCT/GB97/02325 and US Patent Serial (1999), No 09/147773Gibson, I.R., (1999) J. Biomed. Mat. Res, 44, p. 422; Botelho, C.M., (2002) J. Mater. Sci:Mater. Med, 13, pp. 1123-1127; Muller, (1999) Macromol. Rapid Commun, 20, pp. 607-611; Veerman, (1987) Biomaterials, 8, pp. 442-448; Haynes, in Colloids and Surfaces B (1994) Biointerfaces, 2, pp. 517-566; Reffit, D.M., (2003) Bone, 32, p. 127
Keywords: Adsorption; Bioactivity; Bovine collagen type I; Bovine collagens; Bovine serum proteins; Collagen; Human serum proteins; hydroxyapatite; Immunoglobulin G (IgG); immunology; Silicon-substituted hydroxyapatite; Substitution reactions; Tissue culture

In vitro biodegradability of chitosan-organosiloxane hybrid membrane - Tsuru, K.; Shirosaki, Y.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Fernandas, M.H. (Key Engineering MaterialsKey Eng Mat, 2005)
Chitosan-silicate hybrid membranes were prepared using γ- glycidoxypropyltrimethoxysilane (GPSM) through a sol-gel process. The amino groups of chitosan chains were reacted with the epoxy groups of GPSM and GPSM have a function as the agent to cross-link the chitosan chains. The cross-linking degree of the hybrid membranes was determined by ninhydrin assay. Fourier-transform infrared (FT-IR) spectroscopy and 29Si cross-polarization (CP) magic-angle spinning (MAS)-NMR spectroscopy were used to assess the structure of the hybrid membranes. The biodegradability of the hybrid membranes in phosphate-buffered saline solution or lysozyme solution was investigated as a function of the GPSM concentration.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Tsuru, K.; Faculty of Engineering, Biomaterial Laboratory, Okayama University, Tsushima, Okayama 700-8530, Japan; email: kanji@cc.okayama-u.ac.jpReferences: Chandy, T., Sharma, P.C., (1990) Biomat Art Cells Art Org, 18, pp. 1-24;Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., (2001) J Ceram Soc Japan, 109, pp. 403-408; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., (2002) Biomaterials, 23, pp. 4765-4773; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2004) Key Engineering Materials, 254-256, pp. 857-860; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2005) Biomaterials, 26, pp. 485-493; S. Prochazkova, K. M. Vårum, K. Østgaard, Carbohydrate Polymers, 38 (1999), p. 115-122Brinker, J.C., Scherer, G.W., (1989) Sol-Gel Science, The Physics and Chemistry of Sol-Gel Processing, , Academic Press, San Diego
Keywords: biodegradability; Biological membranes; chitosan; Chitosan chains; Chitosan inorganic hybrid membranes; Chitosan-lnorganlc hybrid; Crosslinking; Fourier transform infrared spectroscopy; Nuclear magnetic resonance spectroscopy; R- glycidoxypropyltrimethoxysilane GPSM; Reaction kinetics; Silicates; Sol-gel process

In vitro cytocompatibility of MG63 cells on chitosan-organosiloxane hybrid membranes - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Fernandes, M.H. (BiomaterialsBiomaterials, 2005)
Chitosan-silicate hybrids were synthesized using γ- glycidoxypropyltrimethoxysilane (GPSM) as the agent for cross-linking the chitosan chains. CaCl 2 was introduced in the hybrids in expectation that it would improve cell adhesion and differentiation of the hybrid surfaces. Fourier-transform infrared (FT-IR) spectroscopy and 29Si CP-MAS NMR spectroscopy were used to analyze the structures of the hybrids. Cytocompatibility of the hybrids was investigated in terms of proliferation of an osteoblastic cell line, MG63. The adhesion and proliferation of the osteoblastic cells cultured on the surface of a chitosan-GPSM hybrid without calcium were similar to those on a control culture plate, and were better than those on a chitosan membrane. The ALP activity of the cells cultured on this hybrid was higher than that on the chitosan membrane. Contrary to expectations, the incorporation of calcium ions into the hybrids did not improve cell attachment and proliferation on their surfaces. © 2004 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 55Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2004.02.056PubMed ID: 15276356Language of Original Document: EnglishCorrespondence Address: Hayakawa, S.; Biomaterial Laboratory, Faculty of Engineering, Okayama Univ., 3-1-1 T., Okayama-shi, Japan; email: satoshi@cc.okayama-u.ac.jpChemicals/CAS: calcium chloride, 10043-52-4; Alkaline Phosphatase, EC 3.1.3.1; Biocompatible Materials; Calcium, 7440-70-2; Chitosan, 9012-76-4; Cross-Linking Reagents; gamma-glycidoxypropyltrimethoxysilane, 2530-83-8; Membranes, Artificial; Neoplasm Proteins; SilanesManufacturers: Chisso, Japan; Kasei, JapanReferences: Park, J.B., Lakes, R.S., (1992) Biomaterials An Introduction, pp. 223-234. , New York: Plenum Press;Wise, D.L., (2000) Biomaterials and Bioengineering Handbook, pp. 556-559. , New York: Marcel Dekker; Lee, Y.K., Mooney, J.D., Hydrogels for tissue engineering (2001) Chem Rev, 101, pp. 1869-1879; Park, S.N., Park, J.C., Kim, H.O., Song, M.J., Suh, H., Characterization of porous collagen/hyaluronic acid scaffold modified by 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide cross-linking (2002) Biomaterials, 23, pp. 1205-1212; Kuo, C.K., Ma, P.X., Ionically crosslinked alginate hydrogels as scaffolds for tissue engineering: Part 1 Structure, gelation rate and mechanical properties (2001) Biomaterials, 22, pp. 511-521; Widmer, M.S., Gupta, P.K., Lu, L., Meszlenyi, R.K., Evans, G.R.D., Brandt, K., Savel, T., Mikos, A.G., Manufacture of porous biodegradable polymer conduits by an extrusion process for guided tissue regeneration (1998) Biomaterials, 19, pp. 1945-1955; Wang, Y.C., Lin, M.C., Wang, D.M., Hsieh, H.J., Fabrication of a novel porous PGA-chitosan hybrid matrix for tissue engineering (2003) Biomaterials, 24, pp. 1047-1057; Domard, A., Rinaudo, M., Preparation and characterization of fully deacetylated chitosan (1983) Int J Biol Macromol, 5, pp. 49-52; Chandy, T., Sharma, P.C., Chitosan - As a biomaterial (1990) Biomater Artif Cells Artif Organo, 18, pp. 1-24; Ueno, H., Yamada, H., Tanaka, I., Kaba, N., Matsuura, M., Okumura, M., Kadosawa, T., Fujinaga, T., Accelerating effects of chitosan for healing at early phase of experimental open wound in dogs (1999) Biomaterials, 20, pp. 1407-1414; Varma, H.K., Yokogawa, Y., Espinosa, F.F., Kawamoto, Y., Nishizawa, K., Nagata, F., Kameyama, T., Porous calcium phosphate coating over phosphorylated chitosan film by a biomimetic method (1999) Biomaterials, 20, pp. 879-884; Xiao, C., Gao, S., Wang, H., Zhang, L., Blend films from chitosan and konjac glucomannan solutions (2000) J Appl Polym Sci, 76, pp. 509-515; Chung, T.W., Lu, Y.F., Wang, S.S., Lin, Y.S., Chu, S.H., Growth of human endothelial cells on photochemically grafted Gly-Arg-Gly-Asp (GRGD) chitosans (2002) Biomaterials, 23, pp. 4803-4809; Muzzareli, R.A.A., Mattioli-Belmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Fini, M., Biagini, G., Stimulatory effect on bone formation exerted by a modified chitosan (1994) Biomaterials, 15, pp. 1075-1081; Park, Y.J., Lee, M.Y., Lee, J.Y., Seol, Y.J., Chung, C.P., Lee, S.J., Controlled release of platelet-derived growth factor-BB from chondroitin sulfate-chitosan sponge for guided bone regeneration (2000) J Controlled Rel, 67, pp. 385-394; Suzuki, T., Mizushima, Y., Umeda, T., Ohashi, R., Further biocompatibility testing of silica-chitosan complex membrane in the production of tissue plasminogen activator by epithelial and fibroblast cells (1999) J Biosci Bioeng, 88, pp. 194-199; Yamaguchi, I., Itoh, S., Suzuki, M., Sakane, M., Osaka, A., Tanaka, J., The chitosan prepared from crab tendon I: The characterization and the mechanical properties (2003) Biomaterials, 24, pp. 2031-2036; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., Enhanced bone formation by controlled growth factor delivery from chitosan-based biomaterials (2002) J Controlled Rel, 78, pp. 187-197; Kawamura, Y., Mitsuhashi, M., Tanibe, H., Yoshida, H., Adsorption of metal ions on polyaminated highly porous chelating resin (1993) Ing Eng Chem Res, 32, pp. 386-391; Jameela, S.R., Jayakrishnan, A., Glutaraldehyde crosslinked chitosan as a long acting biodegradable drug delivery vehicle: Studies on the in vitro release of mitoxantrone and in vivo degradation of microspheres in rat muscle (1995) Biomaterials, 16, pp. 769-775; Speer, D.P., Chvapil, M., Eskelson, C.D., Ulreich, J., Biological effects of residual glutaraldehyde in glutaraldehyde-tanned collagen biomaterials (1980) J Biomed Mater Res, 14, pp. 753-764; Nishi, C., Nakajima, N., Ikada, Y., In vitro evaluation of cytotoxicity of diepoxy compounds used for biomaterial modification (1995) J Biomed Mater Res, 29, pp. 829-834; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Sol-gel preparation and in vitro deposition of apatite on porous gelatin-siloxane hybrids (2001) J Non-Cryst Solid, 285, pp. 116-122; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Novel approach to fabricate porous gelatin-siloxane hybrids for bone tissue engineering (2002) Biomaterials, 23, pp. 4765-4773; Berridge, V., Tan, A.S., Characterization of the cellular reduction of 3-(4,5-dimethylthiazol-2- yl)-2,5-diphenyltetrazolium bromide (MTT) subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch Biochem Biophys, 303, pp. 474-482; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Incorporation of Ca 2+ ions in gelatin-siloxane hybrids through a sol-gel process (2001) J Ceramic Soc Japan, 109, pp. 403-408; Yamaguchi, I., Tokuchi, K., Fukuzaki, H., Koyama, Y., Takakuda, K., Monma, H., Tanaka, J., Preparation and microstructure analysis of chitosan/hydroxyapatite nanocomposites (2001) J Biomed Mater Res, 55, pp. 20-27; Hench, L.L., Ethridge, E.C., (1982) Biomaterias An Interfacial Approach, p. 10. , New York: Academic Press; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Martin, T.J., Findlay, D.M., Heath, J.K., Ng, K.W., Osteoblasts: Differentiation and function (1993) Handbook of Experimental Pharmacology, pp. 149-183. , J.R. Mundy, & T.J. Martin. Berlin: Springer; Aubin, J.E., Turksen, K., Heersch, J.N.M., Osteoblastic cell lineage (1993) Cellular and Molecular Biology of Bone, pp. 1-45. , M. Noda. Tokyo: Academic Press Inc; Anderson, S.I., Downes, S., Perry, C.C., Caballero, A.M., Evaluation of the osteoblast response to a silica gel in vitro (1998) J Mater Sci: Mater Med, 9, pp. 731-735; Rhee, S.H., Hwang, M., Si, H.J., Choi, J.Y., Biological activities of osteoblasts on poly(methyl methacrylate)/silica hybrid containing calcium salt (2003) Biomaterials, 24, pp. 901-906; Kalonji, E.E., Denis, I., Lieberherr, M., Pointillart, A., Effects of extracellular calcium on the proliferation and differentiation of porcine osteoblasts in vitro (1998) Cell Tissue Res, 292, pp. 163-171; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of pre-immersion on the biocompatibility of glass-reinforced hydroxyapatite plasma-sprayed coatings (2000) Biomaterials, 21, pp. 813-820; Bilezikian, J.P., Raisz, L.G., Rodan, G.A., (2002) Principles of Bone Biology, p. 1325. , New York: Academic Press
Keywords: alkaline phosphatase; article; artificial membrane; Biocompatibility; Biocompatible Materials; Bone Neoplasms; Calcium; calcium chloride; cell adhesion; Cell attachments; Cell culture; cell differentiation; Cell Division; Cell Line, Tumor; chitosan; chitosan derivative; controlled study; cross linking; Cross-Linking Reagents; Crosslinking; Cytocompatibility; Fourier transform infrared spectroscopy; human; human cell; Humans; hybrid; infrared spectroscopy; Magnetic Resonance Spectroscopy; materials testing; Membranes, Artificial; MG63 osteoblastic cells; Microscopy, Electron, Scanning; Neoplasm Proteins; Nuclear magnetic resonance spectroscopy; Organic-inorganic hybrid; osteoblast; Osteoblasts; Osteosarcoma; priority journal; Silanes; Silicates; siloxane; Spectroscopy, Fourier Transform Infrared; structure analysis; surface property; Synthesis (chemical); wettability; γ-Glycidoxypropyltrimethoxysilane (GPSM)

In vitro studies of calcium phosphate glass ceramics with different solubility with the use of human bone marrow cells - Dias, A.G.; Lopes, M.A.; Trigo Cabral, A.T.; Santos, J.D.; Fernandes, M.H. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2005)
Two glass ceramics in the CaO-P 2O 5-MgO system with the incorporation of K 2O or TiO 2 oxides were prepared with the goal of using them as potential bone graft substitutes. The incorporation of TiO 2 and K 2O led to the preparation of specific crystalline phases in the structure of the glass ceramics, which show different degrees of biodegradation. In fact, the 45CaO-45P 2O 5-5MgO-5K 2O has been previously demonstrated to be much more soluble in aqueous solutions than the 45CaO-37P 2O 5-5MgO-13TiO 2 glass ceramic. The in vitro biological activity of the two calcium phosphate glass ceramics was studied with the use of human bone marrow osteoblast cell cultures maintained for 28 days, and seeded materials were assessed for cell proliferation and function. The Ti-containing glass ceramic showed a stable surface throughout the culture time, on macroscopic and SEM observation. Osteoblast cells proliferated gradually, especially during the third week, with a high alkaline phosphatase activity and formation of a mineralized matrix. On SEM observation, attached cells appeared with a spreadpolygonal morphology typical of the osteoblast cells, with extensive cell-to-cell contact. Cell behavior on the seeded material was similar to that found on cultures performed on tissue-culture-grade polystyrene; except for the presence of lower cell numbers during the first 2 weeks. By contrast, the K-containing glass ceramic showed a highly instable surface with dissolution/precipitation processes occurring throughout the culture time. Few cells adhered to the material surface, and subsequent proliferation was also hindered, especially from the first week onwards. Cell numbers were significantly lower than those observed in the Ti-containing glass ceramic during most of the incubation time. Results suggest that the different in vitro biological behavior of these two glass ceramics is mainly due to the significant differences in the surface degradation rate, which is directly correlated to the chemical composition of the mother glass. © 2005 Wiley Periodicals, Inc.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30357PubMed ID: 15988737Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; FMDUP-Faculdade de Medicina Dentária da Universidade do Porto, Rua Dr. Manuel Pereira da Silva, 4200 Porto, Portugal; email: mhrf@portugalmail.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; polystyrene, 9003-53-6; titanium dioxide, 1317-70-0, 1317-80-2, 13463-67-7, 51745-87-0; Alkaline Phosphatase, EC 3.1.3.1; calcium phosphate, 10103-46-5; Calcium Phosphates; Ceramics; Glass ceramics, 85422-94-2References: Yaszemski, M.J., Payne, R.G., Hayes, W.C., Langer, R., Mikos, A.C., Evolution of bone transplantation: Molecular, cellular and tissue strategies to engineer human bone (1996) Biomaterials, 17, pp. 175-185;Rueger, J.M., Bone replacement materials-state of the art and the way ahead (1998) Orthopade, 27, pp. 72-79; Tadic, D., Epple, M., A thorough physicochemical characterization of 14 calcium phosphate-based bone substitution materials in comparison to natural bone (2004) Biomaterials, 25, pp. 987-994; Greenwald, A.C., Bolden, S.D., Goldberg, V.M., Khan, Y., Laurencin, C.T., Rosier, R.N., Bone-graft substitutes: Facts, fictions and applications (2001) J Bone Joint Surg, 83 A, pp. 98-103; Damien, C.J., Parson, J.R., Bone graft and bone graft substitutes: A review of current technology and applications (1997) J Appl Biomater, 2, pp. 187-208; Lettuec, J.C., Clément, D., Lesprit, E., Faber, J., The use of calcium phosphates, their biological properties (2000) Eur J Orthop Surg Traumatol, 10, pp. 223-229; Dorozhkin, S.V., Epple, M., Biological and medical significance of calcium phosphates (2002) Angew Chem Int Ed Engl, 41, pp. 3130-3146; Dias, A.G., Lopes, M.A., Gibson, I.R., Santos, J.D., In vitro degradation studies of calcium phosphate glass ceramics prepared by controlled crystallization (2003) J Non-Cryst Solids, 330, pp. 81-89; Fini, M., Giardino, R., In vitro and in vivo tests for the biological evaluation of candidate orthopedic materials: Benefits and limits (2003) J Appl Biomater Biomech, 1, pp. 155-163; Hunt, J.A., McLaughlin, P.J., Flanagan, B.F., Review-Techniques to investigate cellular and molecular interaction in the host response to implanted biomaterials (1997) Biomaterials, 18, pp. 1449-1459; Dias, A.G., Tsuru, K., Hayakawa, S., Lopes, M.A., Santos, J.D., Osaka, A., Crystallization studies of biodegradable CaO-P 2O 5 glass with MgO and TiO 2 for bone regeneration applications (2004) Glass Technol, 45; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681; Kumari, T.V., Vasudev, U., Kumar, A., Menon, B., Cell surface interactions in the study of biocompatibility (2002) Trends Biomater Artif Organs, 15, pp. 37-41; Sun, J.S., Tsuang, Y.H., Liao, C.J., Liu, H.C., Hang, Y.S., Lin, F.H., The effects of calcium phosphate particles on the growth of osteoblasts (1997) J Biomed Mater Res, 37, pp. 324-334; Sun, J.S., Whs, C., Chen, L.T., Huang, Y.C., Juang, L.W., Lin, F.H., The influence on gene-expression profiling of osteoblasts behavior following treatment with the ionic products of sintered β-dicalcium pyrophosphate dissolution (2004) Biomaterials, 25, pp. 607-616; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II: Effect of ascorbic acid b-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Morais, S., Dias, N., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro osteoblastic differentiation of human bone marrow cells in the presence of metal ions (1999) J Biomed Mater Res, 44, pp. 176-190; Coelho, M.J., Cabral, A.T., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part I: Osteoblastic differentiation of serially passaged human bone marrow cells cultured in alpha-MEM and in DMEM (2000) Biomaterials, pp. 211087-211094; Dias, A.G., Lopes, A.G., Santos, J.D., Fernandes, N.H., The influence of pre-incubation treatment in the in vitro biological performance of degradable CaO-P 2O 5 glass ceramics (2005) Key Eng Mater, 284-286, pp. 565-568; Bitar, M., Salih, V., Mudera, V., Knowles, J.C., Lewis, M.P., Soluble phosphate glasses: In vitro studies using human cells of hard and soft tissue origin (2004) Biomaterials, 25, pp. 2283-2292; Suzuki, T., Yamamoto, T., Toriyana, M., Nishizawa, K., Yokogawa, Y., Mucalo, M.R., Kawamoto, Y., Kameyama, T., Surface instability of calcium phosphate ceramics in tissue growth of anchorage-dependent animal cells (1997) J Biomed Mater Res, 34, pp. 507-517; Ducheyne, P., Qiu, Q., Bioactive ceramics: The effect of surface reactivity on bone formation and bone cell function (1999) Biomaterials, 20, pp. 2287-2303; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Mineral, 14, pp. 27-40; Stein, G.S., Lian, J.B., Stein, J.L., Van Wijnen, A.J., Frenkel, B., Montecino, M., Mechanism regulating osteoblast proliferation and differentiation (1996) Principles of Bone Biology, pp. 69-83. , Bilezikian JP, Raisz LG, Rodan GA, editors. New York: Academic Press; Chun, S., Na, S.W., Lee, J.H., Chung, J.P., Ryu, I.C., Kim, S.Y., Biodegradation study of potassium calcium metaphosphate in the SBF and Tris-buffer solution (2002) Key Eng Mater, 218-220, pp. 149-152; Ploska, U., Berger, G., Solubility of compositions in the system CaTi xZr 4 - X(PO 4) 6 with x = 0-4 (1997) Biomaterials, 18, pp. 1671-1675; Dias, A.G., Skakle, J.M.S., Gibson, I.R., Lopes, M.A., Santos, J.D., In situ thermal and structural characterization of bioactive calcium phosphate glass ceramics containing TiO 2 and MgO oxides: HT-XRD studies (2005) J Non-Cryst Solids, , Forthcoming; Chun, S., Jeong, J.H., Kim, K.H., Kim, S., Biodegradation study of amorphous and crystalline calcium metaphosphate in SBF and Tris-buffer solution (2001) Key Eng Mater, 192-195, pp. 131-134; Elghannam, A., Ducheyne, P., Shapiro, I.M., Bioactive material template for in vitro synthesis of bone (1995) J Biomed Mater Res, 29, pp. 359-370; Kitsugi, T.T., Yamamuro, T., Nakamura, T., Oka, M., Transmission electron microscopy observations at the interface of bone and four types of calcium phosphate ceramics with different calcium/phosphorous molar ratios (1995) Biomaterials, 16, pp. 1101-1107; Gross, U., Muller-Mai, C., Voigt, C., Mesgarian, M., Berger, G., Ploska, U., Tissue response in the femur of rabbits after implantation of a new calcium titanium phosphate composition (2001) Key Eng Mater, 192-195, pp. 383-386; Hill, P.A., Orth, M., Bone remodeling - Review (1998) Br J Orthod, 25, pp. 101-107
Keywords: alkaline phosphatase; aqueous solution; article; Biodegradation; Bone; Bone graft; bone marrow cell; Bone Marrow Cells; bone mineralization; bone prosthesis; Calcium Compounds; calcium phosphate; Calcium phosphate glass ceramic; Calcium phosphate glass ceramics; Calcium phosphates; cell contact; Cell culture; cell proliferation; Cells; ceramics; chemical composition; controlled study; crystal structure; Dissolution; enzyme activity; extracellular matrix; glass; Glass ceramics; human; Human bone marrow cells; human cell; Humans; in vitro study; In vitro testing; Magnesia; magnesium derivative; Microscopy, Electron, Scanning; osteoblast; Osteoblasts; polystyrene; Precipitation (chemical); Scanning electron microscopy; Solubility; Spectrum Analysis; Surface treatment; Titanium dioxide

The influence of pre-incubation treatment in the in vitro biological performance of degradable CaO-P 2O 5 glass ceramics - Dias, A.G.; Lopes, M.A.; Santos, J.D.; Fernandes, M.H. (Key Engineering MaterialsKey Eng Mat, 2005)
Based upon the CaO-P 2O 5 glass system, two glass ceramics were prepared in the meta-, pyro- and orthophosphate regions. The present work describes results concerning the biological activity of MT13B (45CaO-37P 2O 5-5MgO-13TiO 2, in mol %) and MK5B (45CaO-45P 2O 5-5MgO-5K 2O, in mol %) using MG63 osteoblast-like cells cultured for 6 days. The influence of a 24h pretreatment with culture medium before cell culture was also evaluated (MT13Bi; MK5Bi). Both "as-received" and pre-treated material samples supported cell growth, which increased with the culture time. Pre-treatment resulted in an increase of adhered cells on both materials (day 1). Throughout the culture time (days 3 and 6), MT13Bi presented higher cell numbers than that of MT13B, but no differences were found between MK5Bi and MK5B. In addition, cell growth was significantly lower in the K-containing glass ceramic in both experimental situations comparing with Ti-containing glass ceramic. SEM and confocal microscopy observation showed that cell adhesion and spreading were hampered on MK5B samples. Evident macroscopic and microscopic surface instability was observed on this material with simultaneous dissolution/precipitation processes. By contrast, MT13B presented a relatively stable surface throughout the culture time. Results suggest that the pre-incubation with culture medium improves the adhesion of the osteoblast cells to both glass ceramics and that the high degradation rate of MK5B hinders the in vitro biological performance of this material.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Dias, A.G.; FEUP-Faculdade de Engenharia, Universidade do Porto, DEMM, Rua Dr. Roberta Frias, 4200 Porto, Portugal; email: pde99423@fe.up.ptReferences: Damien, C.J., Bone graft and bone graft substitutes a review of current technology and applications (1997) Journal of Applied Biomaterial, 2, pp. 187-208;Dias, A.G., In vitro degradation studies of calcium phosphate glass ceramics prepared by controlled crystallization (2003) Journal of Non-Crystalline Solids, 330 (1-3), pp. 81-89; Dias, A.G., Crystallization studies of biodegradable CaO-P 2O 5 glass with MgO and TiO 2 for bone regeneration applications (2004) Glass Technology, 45 (2), pp. 78-79; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681
Keywords: Bioactivity; biodegradability; Biodegradable glass ceramics; Calcium Compounds; Cell culture; cell growth; Glass ceramics; MG63 osteoblast-like cells; Orthophosphate; Osteoblasts; Pretreatment

Neural network classification: Maximizing zero-error density - Silva, L.M.; Alexandre, L.A.; De Sá, J.M. (Lecture Notes in Computer ScienceLect. Notes Comput. Sci., 2005)
We propose a new cost function for neural network classification: the error density at the origin. This method provides a simple objective function that can be easily plugged in the usual backpropagation algorithm, giving a simple and efficient learning scheme. Experimental work shows the effectiveness and superiority of the proposed method when compared to the usual mean square error criteria in four well known datasets. © Springer-Verlag Berlin Heidelberg 2005.
Conference code: 65875Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Silva, L.M.; Instituto de Engenharia Biomédica, Lab. de Sinai e Imagem Biomédica, Campus da FEUP, Rua Dr. Roberto Frias, 4200 - 465 Porto, PortugalReferences: Erdogmus, D., Principe, J.C., An error-entropy minimization algorithm for supervised training of nonlinear adaptive systems (2002) IEEE Transactions on Signal Processing, 50 (7), pp. 1780-1786;Erdogmus, D., Principe, J., Generalized information potential criterion for adaptive system training (2002) IEEE Transactions on Neural Networks, 13 (5), pp. 1035~1044; Santos, J.M., Alexandre, L.A., Marques De Sá, J., The error entropy minimization algorithm for neural network classification (2004) Int. Conf. on Recent Advances in Soft Computing, , Nottingham, United Kingdom; Santos, J.M., Alexandre, L.A., De Sa, J.M., Optimization of the error entropy minimization algorithm for neural network classification (2004) Intelligent Engineering Systems Through Artificial Neural Networks, 14, pp. 81-86. , C. Dagli, A. Buczak, D. Enke, M. Embrechts, and O. Ersoy, editors, ASME Press Series; Silva, L.M., De Sa, J.M., Alexandre, L.A., Neural network classification using shannon's entropy (2005) European Symposium on Artificial Neural Networks; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, 3, pp. 79-87; Blake, C.L., Merz, C.J., (1998) UCI Repository of Machine Learning Databases, , http://www.ics.uci.edu/~mlearn/MLRepository.html, University of California, Irvine, Dept. of Information and Computer Sciences
Keywords: Algorithms; Backpropagation; Backpropagation algorithm; Classification (of information); Costs; Error analysis; Function evaluation; Learning systems; Mean square error; Neural network classification; Neural networks; Zero-error density

Neural networks trained with the EEM algorithm: Tuning the smoothing parameter - Santos, J.M.; Marques de Sá, J.; Alexandre, L.A. (WSEAS Transactions on SystemsWSEAS Trans. Syst., 2005)
The training of Neural Networks and particularly Multi-Layer Perceptrons (MLP's) is made by minimizing an error function usually known as "cost function". In our previous works, we apply the Error Entropy Minimization (EEM) algorithm in classification and its optimized version using, as cost function, the entropy of the errors between the outputs and the desired targets of the neural network. One of the difficulties in implementing the EEM algorithm is the choice of the smoothing parameter, also known as window size, in the Parzen Window probability density function estimation for the computation of the entropy and its gradient. We present here a formula yielding the value of the smoothing parameter, depending on the number of data samples and on the neural network output dimension. Several experiments with real data sets were made in order to show the validity of the proposed formula.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Santos, J.M.; Intituto de Engenharia Biomédica, Porto, Portugal; email: jms@isep.ipp.ptReferences: Erdogmus, D., Principe, J., "An Error-Entropy Minimization Algorithm for Supervised Training of Nonlinear Adaptive Systems" (2002) Trans. On Signal Processing, 50 (7), pp. 1780-1786;Santos, J.M., Alexandre, L.A., Marques de Sá, J., "The error entropy minimization algorithm for neural network classification" (2004) Proceedings of the 5th International Conference on Recent Advances in Soft Computing, pp. 92-97. , A. Lofti, Ed. Nottingham Trent University; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Sereno, F., "Optimization of the error entropy minimization algorithm for neural network classification" (2004) Intelligent Engineering Systems Through Artificial Neural Networks, 14, pp. 81-86. , C.H. Dagli, A.L. Buczak, D.L. Enke, M.J. Embrechts, and O. Ersoy, Eds., ASME Press; Erdogmus, D., Principe, J., "Entropy Minimization Algorithm for Neural Networks" (2001) Proceedings of the Intl. Joint Conf. on Neural Networks, pp. 3003-3008; Xu, D., Princpe, J., "Training mlps layer-by-layer with the information potential" (1999) Intl. Joint Conf. on Neural Networks, pp. 1716-1720; Silverman, B.W., (1986) Density Estimation for Statistics and Data Analisys, 26. , Chapman & Hall; Bowman, A.W., Azzalini, A., (1997) Applied Smooting Techniques for Data Analysis, , London: Oxford University Press; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., "Adaptive mixtures of local experts" (1991) Neural Computation, pp. 79-87
Keywords: Cost function; entropy; Error entropy minimization (EEM) algorithm; Learning algorithms; Learning systems; Neural networks; Optimization; Parzen; Probability density function; Smoothing parameter

Porous HA scaffolds for drug releasing - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2005)
Dense and porous hydroxyapatite materials aimed at being used in controlled drug delivery, were characterised and studied in order to evaluate their ability to adsorb and release sodium ampicillin in a controlled manner, as a model for a drug delivery system, potentially applicable associated to surgery for the treatment of bone defects. These porous materials should also have adequate mechanical strength to withstand manipulation and sculpturing in surgery room. Adsorption and release profiles were obtained for a range of porous materials, leading to higher adsorption rates and more adequate release profiles than for dense materials.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Queiroz, A.C.; INEB, Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: aqueiroz@ineb.up.ptReferences: Queiroz, A.C., (2001) Biomaterials, 22, p. 1393
Keywords: Adsorption; ampicillin; Controlled drug delivery; Drug release; hydroxyapatite; orthopedics; Porous hydroxyapatite; Porous hydroxyapatites; Porous materials; Scaffolds; Sodium ampicillin; Surgery; Surgery rooms

Proliferation, activity, and osteogenic differentiation of bone marrow stromal cells cultured on calcium titanium phosphate microspheres - Barrias, C.C.; Ribeiro, C.C.; Lamghari, M.; Sá Miranda, C.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2005)
In this study, the behavior of bone marrow stromal cells cultured on calcium titanium phosphate (CTP) microspheres was analyzed. Cell adhesion and proliferation were estimated by the neutral red assay and by total DNA quantification. Morphology and deposition of extracellular matrix were assessed by confocal laser scanning microscopy and/or scanning electron microscopy. The expression of the osteoblastic phenotype was evaluated by monitoring alkaline phosphatase activity and osteocalcin secretion. Results revealed that cells were able to attach and spread on the surface of CTP microspheres, and gradually grow into nearly confluent monolayers. Moreover, cells were able to bridge adjacent microspheres forming microsphere-cell clusters. Cells produced an abundant amount of fibrillar extracellular matrix that covered the substrate surface. Alkaline phosphatase activity peaked around days 7-14 and then decreased until day 21. Cells secreted osteocalcin, with higher levels being detected at day 14 than at day 21. Taken together, these results suggest that CTP microspheres are appropriate scaffolds for the growth and differentiation of cells along the osteoblastic lineage. © 2004 Wiley Periodicals, Inc.
Cited By (since 1996): 34Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30217PubMed ID: 15543603Language of Original Document: EnglishCorrespondence Address: Barrias, C.C.; INEB, Instituto de Engenharia Biomedica, Laboratorio de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: ccbarrias@ineb.up.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; osteocalcin, 136461-80-8; titanium, 7440-32-6; Alkaline Phosphatase, EC 3.1.3.1; Calcium, 7440-70-2; Osteocalcin, 104982-03-8; titanium phosphate, 17017-57-1; Titanium, 7440-32-6References: Senuma, Y., Franceschin, S., Hilborn, J.G., Tissieres, P., Bisson, I., Frey, P., Bioresorbable microspheres by spinning disk atomization as injectable cell carrier: From preparation to in vitro evaluation (2000) Biomaterials, 21 (11), pp. 1135-1144;Hsu, F.Y., Chueh, S.C., Wang, Y.J., Microspheres of hydroxyapatite/ reconstituted collagen as supports for osteoblast cell growth (1999) Biomaterials, 20 (20), pp. 1931-1936; McGlohorn, J.B., Grimes, L.W., Webster, S.S., Burg, K.J., Characterization of cellular carriers for use in injectable tissue-engineering composites (2003) J Biomed Mater Res, 66 A (3), pp. 441-449; Wu, T.J., Huang, H.H., Lan, C.W., Lin, C.H., Hsu, F.Y., Wang, Y.J., Studies on the microspheres comprised of reconstituted collagen and hydroxyapatite (2004) Biomaterials, 25 (4), pp. 651-658; Barrias, C.C., Ribeiro, C.C., Barbosa, M.A., Adhesion and proliferation of human osteoblastic cells seeded on injectable hydroxyapatite microspheres (2004) Key Eng Mater, 254-256, pp. 877-880; Van Wezel, A.L., Microcarrier technology: Present status and prospects (1983) Dev Biol Stand, 55, pp. 3-9; Malda, J., Kreijveld, E., Temenoff, J.S., Van Blitterswijk, C.A., Riesle, J., Expansion of human nasal chondrocytes on macroporous microcarriers enhances redifferendation (2003) Biomaterials, 24 (28), pp. 5153-5161; Frondoza, C., Sohrabi, A., Hungerford, D., Human chondrocytes proliferate and produce matrix components in microcarrier suspension culture (1996) Biomaterials, 17 (9), pp. 879-888; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., A novel route for the preparation of injectable ceramic porous microspheres for bone tissue engineering (2003) Ceramics, Cells and Tissues Annual Conferences: Bioceramic Surfaces Behavior in Vitro and in Vivo, pp. 228-232. , Ravaglioli A, Krajewski A, editors. Faenza: ISTEC-CNR editions; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., (2004) Preparation and Characterisation of Calcium-phosphate Microspheres for Biomedical Applications, , Submitted for publication; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254 (2), pp. 317-330; Labarca, C., Paigen, K., Simple, rapid, and sensitive DNA assay procedure (1980) Anal Biochem, 102 (2), pp. 344-352; Mankani, M.H., Kuznetsov, S.A., Fowler, B., Kingman, A., Robey, P.G., In vivo bone formation by human bone marrow stromal cells: Effect of carrier particle size and shape (2001) Biotechnol Bioeng, 72 (1), pp. 96-107; Higashi, T., Okamoto, H., Influence of particle size of calcium phosphate ceramics as a capping agent on the formation of a hard tissue barrier in amputated dental pulp (1996) J Endod, 22 (6), pp. 281-283; Misiek, D.J., Kent, J.N., Carr, R.F., Soft tissue responses to hydroxylapatite particles of different shapes (1984) J Oral Maxillofac Surg, 42 (3), pp. 150-160; Maniatopoulos, C., Bone formation by young adult bone marrow stromal cells in vitro (1987) J Dent Res, 66, p. 104; Pittenger, M.F., Mackay, A.M., Beck, S.C., Jaiswal, R.K., Douglas, R., Mosca, J.D., Moorman, M.A., Marshak, D.R., Multilineage potential of adult human mesenchymal stem cells (1999) Science, 284 (5411), pp. 143-147; Ter Brugge, P.J., Jansen, J.A., In vitro osteogenic differentiation of rat bone marrow cells subcultured with and without dexamethasone (2002) Tissue Eng, 8 (2), pp. 321-331; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21 (7), pp. 667-681; Anselme, K., Linez, P., Bigerelle, M., Le Maguer, D., Le Maguer, A., Hardouin, P., Hildebrand, H.F., Leroy, J.M., The relative influence of the topography and chemistry of TiA16V4 surfaces on osteoblastic cell behaviour (2000) Biomaterials, 21 (15), pp. 1567-1577; Deligianni, D.D., Katsala, N.D., Koutsoukos, P.G., Missirlis, Y.F., Effect of surface roughness of hydroxyapatite on human bone marrow cell adhesion, proliferation, differentiation and detachment strength (2001) Biomaterials, 22 (1), pp. 87-96; Boyan, B.D., Lossdorfer, S., Wang, L., Zhao, G., Lohmann, C.H., Cochran, D.L., Schwartz, Z., Osteoblasts generate an osteogenic microenvironment when grown on surfaces with rough microtopographies (2003) Eur Cell Mater, 6, pp. 22-27; Brunette, D.M., The effects of implant surface topography on the behavior of cells (1988) Int J Oral Maxillofac Implants, 3 (4), pp. 231-246; Schwartz, Z., Lohmann, C.H., Oefinger, J., Bonewald, L.F., Dean, D.D., Boyan, B.D., Implant surface characteristics modulate differentiation behavior of cells in the osteoblastic lineage (1999) Adv Dent Res, 13, pp. 38-48; Shu, R., McMullen, R., Baumann, M.J., McCabe, L.R., Hydroxyapatite accelerates differentiation and suppresses growth of MC3T3-E1 osteoblasts (2003) J Biomed Mater Res, 67 A (4), pp. 1196-1204; Nordstrom, E., Ohgushi, H., Yoshikawa, T., Yokobori, A.T., Yokobori, T., Osteogenic differentiation of cultured marrow stromal stem cells on surface of microporous hydroxyapatite based mica composite and macroporous synthetic hydroxyapatite (1999) Biomed Mater Eng, 9 (1), pp. 21-26; Oreffo, R.O.C., Driessens, F.C.M., Flanell, J.A., Triffitt, J.T., Growth and differentiation of human bone marrow osteoprogenitors on novel calcium phosphate cements (1998) Biomaterials, 19 (20), pp. 1845-1854; Knabe, C., Berger, G., Gildenhaar, R., Klar, F., Zreiqat, H., The modulation of osteogenesis in vitro by calcium titanium phosphate coatings (2004) Biomaterials, 25, pp. 4911-4919
Keywords: alkaline phosphatase; animal cell; Animals; article; Bioassay; Bone; bone marrow cell; Bone Marrow Cells; bone marrow stromal cell; Bone marrow stromal cells; Calcium; Calcium Compounds; calcium phosphate; Calcium titanium phosphate; cell adhesion; Cell culture; cell differentiation; cell growth; cell lineage; cell proliferation; cell structure; Confluent monolayers; confocal laser microscopy; Confocal laser scanning microscopy; controlled study; Deposition; DNA determination; enzyme activity; Enzyme kinetics; extracellular matrix; Microscopy, Electron; microsphere; Microspheres; nonhuman; osteoblast; osteocalcin; Osteogenesis; Osteogenic differentiation; phenotype; protein expression; protein secretion; rat; Rats; Scanning electron microscopy; Stromal Cells; surface property; Tissue culture; Tissue engineering; Titanium; unclassified drug

Rat bone marrow stromal cell osteogenic differentiation and fibronectin adsorption on chitosan membranes: The effect of the degree of acetylation - Amaral, I.F.; Lamghari, M.; Sousa, S.R.; Sampaio, P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2005)
Cell adhesion, migration, and proliferation of a few anchorage-dependent cells cultured on chitosan (Ch) matrices are influenced by the degree of N-acetylation (DA) of Ch. In the present work, we examined the influence of the DA on the attachment, spreading, proliferation, and osteogenic differentiation of rat bone marrow stromal cells (rBM-SCs). Ch membranes were characterized in terms of surface morphology, roughness, and wettability, and in terms of adsorption of an adhesive protein, fibronectin (Fn). Chs with DAs in the range of 4 to 49% were used. Among the Ch samples, the DA of 4% led to the highest Fn surface concentration, both from single protein solution and from diluted serum. Furthermore, the levels of Fn adsorbed from serum found for this DA were threefold higher than for the tissue culture polystyrene control, indicating that in the presence of competitive proteins Ch is more specific toward Fn adsorption than tissue culture polystyrene. rBMSCs cultured on Ch carrying a DA of 4% were able to spread, proliferate, and differentiate, reaching a higher level of osteogenic differentiation than on the control, despite the lower cell attachment observed for all Ch samples. Because the Ch sample with a DA of 4% showed the highest Fn adsorption from serum, we suggest that cell adhesion, spreading, and osteogenic differentiation of rBMSCs on Ch may be mediated by the adsorbed layer of Fn. © 2005 Wiley Periodicals, Inc.
Cited By (since 1996): 25Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30436PubMed ID: 16092111Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; fibronectin, 86088-83-7; polystyrene, 9003-53-6; Chitosan, 9012-76-4; Coated Materials, Biocompatible; FibronectinsReferences: VandeVord, P.J., Matthew, H.W.T., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., Evaluation of the biocompatibility of a chitosan scaffold in mice (2002) J Biomed Mater Res, 59 (3), pp. 585-590;Muzzarelli, R.A.A., Human enzymatic activities related to the therapeutic administration of chitin derivatives (1997) Cell Mol Life Sci, (53), pp. 131-140; Peluso, G., Petillo, O., Ranieri, M., Santin, M., Ambrosio, L., Calabro, D., Avallone, B., Balsamo, G., Chitosan-mediated stimulation of macrophage function (1994) Biomaterials, 15 (15), pp. 1215-1220; Muzzarelli, R.A.A., Mattiolibelmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Fini, M., Biagini, G., Stimulatory effect on bone-formation exerted by a modified chitosan (1994) Biomaterials, 15 (13), pp. 1075-1081; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., Enhanced bone formation by controlled growth factor delivery from chitosan-based biomaterials (2002) J Controlled Release, 78 (1-3), pp. 187-197; Chupa, J.M., Foster, A.M., Sumner, S.R., Madihally, S.V., Matthew, H.W.T., Vascular cell responses to polysaccharide materials: In vitro and in vivo evaluations (2000) Biomaterials, 21 (22), pp. 2315-2322; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., Chitosan supports the expression of extracellular matrix proteins in human osteoblasts and chondrocytes (2000) J Biomed Mater Res, 51 (4), pp. 586-595; Klokkevold, P.R., Vandemark, L., Kenney, E.B., Bernard, G.W., Osteogenesis enhanced by chitosan (poly-N-acetyl glucosaminoglycan) in vitro (1996) J Periodontol, 67 (11), pp. 1170-1175; Tomihata, K., Ikada, Y., In vitro and in vivo degradation of films of chitin and its deacetylated derivatives (1997) Biomaterials, 18 (7), pp. 567-575; Chatelet, C., Damour, O., Domard, A., Influence of the degree of acetylation on some biological properties of chitosan films (2001) Biomaterials, 22 (3), pp. 261-268; Dhiman, H.K., Ray, A.R., Panda, A.K., Characterization and evaluation of chitosan matrix for in vitro growth of MCF-7 breast cancer cell lines (2004) Biomaterials, 25 (21), pp. 5147-5154; Prasitsilp, M., Jenwithisuk, R., Kongsuwan, K., Damrongchai, N., Watts, P., Cellular responses to chitosan in vitro: The importance of deacetylation (2000) J Mater Sci Mater Med, 11 (12), pp. 773-778; Rainaldi, G., Filippini, P., Ferrante, A., Indovina, P.L., Santini, M.T., Fibronectin facilitates adhesion of K562 leukemic cells normally growing in suspension to cationic surfaces (2001) J Biomed Mater Res, 55 (1), pp. 104-113; Faucheux, N., Schweiss, R., Lutzow, K., Werner, C., Groth, T., Self-assembled monolayers with different terminating groups as model substrates for cell adhesion studies (2004) Biomaterials, 25 (14), pp. 2721-2730; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., Adhesive protein interactions with chitosan: Consequences for valve endothelial cell growth on tissue-engineering materials (2003) J Biomed Mater Res, 67 A (2), pp. 538-547; Bumgardner, J.D., Wiser, R., Elder, S.H., Jouett, R., Yang, Y., Ong, J.L., Contact angle, protein adsorption and osteoblast precursor cell attachment to chitosan coatings bonded to titanium (2003) J Biomater Sci Polym Ed, 14 (12), pp. 1401-1409; Gong, H.P., Zhong, Y.H., Li, J.C., Gong, Y.D., Zhao, N.M., Zhang, X.F., Studies on nerve cell affinity of chitosan-derived materials (2000) J Biomed Mater Res, 52 (2), pp. 285-295; Benesch, J., Tengvall, P., Blood protein adsorption onto chitosan (2002) Biomaterials, 23 (12), pp. 2561-2568; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42 (8), pp. 3569-3580; Mima, S., Miya, M., Iwamoto, R., Yoshikawa, S., Highly deacetylated chitosan and its properties (1983) J Appl Polym Sci, 28 (6), pp. 1909-1917; Aiba, S., Studies on chitosan: 1. Determination of the degree of N-acetylation of chitosan by ultraviolet spectrophotometry and gel-permeation chromatography (1986) Int J Biol Macromol, 8 (3), pp. 173-176; Baxter, A., Dillon, M., Taylor, K.D.A., Roberts, G.A.F., Improved method for i.r. determination of the degree of N-acetylation of chitosan (1992) Int J Biol Macromol, 14 (3), pp. 166-169; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., Molecular parameters of chitosans depolymerized with the aid of papain (1996) Carbohydr Polym, 29 (1), pp. 63-68; Grundke, K., Bogumil, T., Werner, C., Janke, A., Poschel, K., Jacobasch, H.J., Liquid-fluid contact angle measurements on hydrophilic cellulosic materials (1996) Colloids Surf A, 116 (1-2), pp. 79-91; Slack, M., Properties of biological fluids (2004) Biomaterials Science: An Introduction to Materials in Medicine, pp. 813-817. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE, editors. Amsterdam: Elsevier; Du, Y.J., Cornelius, R.M., Brash, J.L., Measurement of protein adsorption to gold surface by radioiodination methods: Suppression of free iodide Sorption (2000) Colloids Surf B, 17 (1), pp. 59-67; (1993) Iodine-125, a Guide to Radioiodination Techniques, p. 64. , Little Chalfont, Buckinghamshire, UK: Amersham International; Sousa, S.R., Moradas-Ferreira, P., Saramago, B., Melo, L.V., Barbosa, M.A., Human serum albumin adsorption on TiO2 from single protein solutions and from plasma (2004) Langmuir, 20 (22), pp. 9745-9754; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone-formation in vitro by stromal cells obtained from bone-marrow of young-adult rats (1988) Cell Tissue Res, 254 (2), pp. 317-330; Ashton, B.A., Abdullah, F., Cave, J., Williamson, M., Sykes, B.C., Couch, M., Poser, J.W., Characterization of cells with high alkaline-phosphatase activity derived from human-bone and marrow: Preliminary assessment of their osteogenicity (1985) Bone, 6 (5), pp. 313-319; Huang, R.Y.M., Moon, G.Y., Pal, R., Chitosan/anionic surfactant complex membranes for the pervaporation separation of methanol/MTBE and characterization of the polymer/surfactant system (2001) J Membr Sei, 184 (1), pp. 1-15; Domke, J., Dannohl, S., Parak, W.J., Muller, O., Aicher, W.K., Radmacher, M., Substrate dependent differences in morphology and elasticity of living osteoblasts investigated by atomic force microscopy (2000) Colloids Surf B, 19 (4), pp. 367-379; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21 (7), pp. 667-681; Domard, A., Chitosan interactions (1997) Advances in Chitin Science, pp. 410-420. , Domard A, Roberts GAF, Varum KM, editors. Lyon, France: Jacques André Publisher; Smidsrod, O., Ottoy, M.H., Anthonsen, M.W., Varum, K.M., Solution properties of chitosan (1997) Advances in Chitin Science, pp. 402-409. , Domard A, Roberts GAF, Varum KM, editors. Lyon, France: Jacques André Publisher; Fee, M., Errington, N., Jumel, K., Ilium, L., Smith, A., Harding, S.E., Correlation of SEC/MALLS with ultracentrifuge and viscometric data for chitosans (2003) Eur Biophys J, 32, pp. 457-464; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) J Biomed Mater Res, 66 A (2), pp. 247-259; Andrade, J.D., Smith, L.M., Gregonis, D.E., The contact angle and interface energetics (1997) Physical Chemistry of Surfaces, pp. 249-292. , Adamson AW, Gast AP, editors. New York: John Wiley & Sons;; McFarland, C.D., Mayer, S., Scotchford, C., Dalton, B.A., Steele, J.G., Downes, S., Attachment of cultured human bone cells to novel polymers (1999) J Biomed Mater Res, 44 (1), pp. 1-11; Lebaron, R.G., Athanasiou, K.A., Extracellular matrix cell adhesion peptides: Functional applications in orthopedic materials (2000) Tissue Eng, 6 (2), pp. 85-103; Massia, S.P., Hubbell, J.A., An RGD spacing of 440 run is sufficient for integrin alpha-V-beta-3- mediated fibroblast spreading and 140 nm for focal contact and stress fiber formation (1991) J Cell Biol, 114 (5), pp. 1089-1100; Verrier, S., Fallu, S., Bareille, R., Jonczyk, A., Meyer, J., Dard, M., Amedee, J., Function of linear and cyclic RGD-containing peptides in osteoprogenitor cells adhesion process (2002) Biomaterials, 23 (2), pp. 585-596; Gronthos, S., Sirnmons, P.J., Graves, S.E., Robey, P.G., Integrin-mediated interactions between human bone marrow stromal precursor cells and the extracellular matrix (2001) Bone, 28 (2), pp. 174-181; Webb, K., Hlady, V., Tresco, P.A., Relationships among cell attachment, spreading, cytoskeletal organization, and migration rate for anchorage-dependent cells on model surfaces (2000) J Biomed Mater Res, 49 (3), pp. 362-368; Stein, G.S., Lian, J.B., Stein, J.L., Wijnen, A.J., Frenkel, B., Montecino, M., Mechanisms regulating osteoblast proliferation and differentiation (1996) Principles of Bone Biology, pp. 69-86. , Bilezikian JP, Raisz LG, Rodan GA, editors. San Diego: Academic Press; Aubin, J.E., Liu, F., The osteoblast lineage (1996) Principles of Bone Biology, pp. 51-67. , Bilezikian JP, Raisz LG, Rodan GA, editors. San Diego: Academic Press; Moursi, A.M., Globus, R.K., Damsky, C.H., Interactions between integrin receptors and fibronectin are required for calvarial osteoblast differentiation in vitro (1997) J Cell Sci, 110, pp. 2187-2196; Stephansson, S.N., Byers, B.A., Garcia, A.J., Enhanced expression of the osteoblastic phenotype on substrates that modulate fibronectin conformation and integrin receptor binding (2002) Biomaterials, 23 (12), pp. 2527-2534
Keywords: Acetylation; Adhesion; Adsorption; animal cell; Animals; article; artificial membrane; binding affinity; binding competition; Bone; bone development; bone marrow cell; Bone Marrow Cells; Bone marrow stomal cells; Bone marrow stromal cells; cell adhesion; cell anchorage; Cell culture; cell differentiation; Cell membranes; cell migration; cell proliferation; Cell Shape; cell spreading; chitosan; Coated Materials, Biocompatible; controlled study; cytoskeleton; Degree of acetylation; Fibronectin; Fibronectins; male; materials testing; morphology; nonhuman; polystyrene; Proteins; rat; Rats; Rats, Wistar; roughness; stroma cell; Stromal Cells; Surface Properties; surface property; Tissue culture; wettability

Recombinant glucocerebrosidase uptake by Gaucher disease human osteoblast culture model - Lamghari, M.; Barrias, C.C.; Sá Miranda, C.; Barbosa, M.A. (Blood Cells, Molecules, and DiseasesBlood Cells Mol. Dis., 2005)
Bone lesions are a major cause of morbidity in Gaucher disease (GD) type I. Enzyme replacement therapy (ERT) has been successful in treating many symptoms of type I GD but skeletal response lags behind. Local exogenous glucocerebrosidase supplementation in bone lesions via a drug delivery system may overcome this limitation. Although local enzyme supplementation aims to target lipid-engorged macrophages (Gaucher Cells) in bone compartment, enzyme uptake by osteoblasts is not excluded. To investigate the ability of human osteoblasts to internalize recombinant glucocerebrosidase (rGCR), we have used an artificial GD human osteoblasts cell culture system. MG63 human osteoblasts were treated with conduritol B epoxide (CBE) to induce complete and prolonged inhibition of endogenous glucocerebrosidase activity of cells. rGCR uptake by glucocerebrosidase-inactivated osteoblasts was examined using 125I-radiolabelling, Western blot analysis and measurement of glucocerebrosidase activity. Analysis of radiolabeled enzyme uptake by CBE treated osteoblasts showed 67.9% of internalized protein in cell extract. Enzyme internalization was also observed by Western blot analysis where the amount of mature form of glucocerebrosidase protein recognized by the glucocerebrosidase antibody was increased following the administrations of rGCR. Moreover, enzymatic activity measurement showed 23.9% of glucocerebrosidase activity of control cells. The rGCR internalization by MG63 osteoblast seems to be partially mediated by mannose receptors. These data provide evidence that MG63 human osteoblasts are able to internalize rGCR. © 2005 Elsevier Inc. All rights reserved.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: BCMDFdoi: 10.1016/j.bcmd.2005.07.009PubMed ID: 16125984Language of Original Document: EnglishCorrespondence Address: Lamghari, M.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, R. Campo Alegre 823, 4150-180 Porto, Portugal; email: lamghari@ineb.up.ptChemicals/CAS: conduritol b epoxide, 6090-95-5; imiglucerase, 154248-97-2; iodine 125, 14158-31-7, 22822-81-7; conduritol epoxide, 6090-95-5; Glucosylceramidase, EC 3.2.1.45; Inositol, 6917-35-7; Recombinant ProteinsTradenames: cerezyme, GenzymeManufacturers: GenzymeReferences: Beutler, E., Grabowski, G., Gaucher disease (1995) The Metabolic and Molecular Bases of Inherited Disease, 2, pp. 2641-2661. , C.R. Scriber A.L. Beaudet W.S. Sly 7th ed. McGraw-Hill New York, NY;Beutler, E., Enzyme replacement in Gaucher disease (2004) PLoS Med., 1 (2), p. 21; Elstein, D., Itzchaki, M., Mankin, H., Skeletal involvement in Gaucher's disease (1997) Ballière's Clin. Haematol., 10 (4), pp. 793-815; Wenstrup, R.J., Roca-Espiau, M., Weinreb, N.J., Bembi, B., Skeletal aspects of Gaucher disease: A review (2002) Br. J. Radiol., 75 (1 SUPPL.), pp. 2-A12; Barranger, J.A., O'Rourke, E., Lessons learned from the development of enzyme therapy for Gaucher disease (2001) J. Inherited Metab. Dis., 24 (2 SUPPL.), pp. 89-96; Zimran, A., Elstein, D., Levy-Lahad, E., Zevin, S., Hadas-Halpern, I., Bar-Ziv, Y., Foldes, J., Abrahamov, A., Replacement therapy with imiglucerase for type 1 Gaucher's disease (1995) Lancet, 345 (8963), pp. 1479-1480; Barton, N.W., Brady, R.O., Dambrosia, J.M., Di Bisceglie, A.M., Doppelt, S.H., Hill, S.C., Mankin, H.J., Argoff, C.E., Replacement therapy for inherited enzyme deficiency-macrophage-targeted glucocerebrosidase for Gaucher's disease (1991) N. Engl. J. Med., 324 (21), pp. 1464-1470; Barton, N.W., Furbish, F.S., Murray, G.J., Garfield, M., Brady, R.O., Therapeutic response to intravenous infusions of glucocerebrosidase in a patient with Gaucher disease (1990) Proc. Natl. Acad. Sci. U. S. A., 87 (5), pp. 1913-1916; Friedman, B., Vaddi, K., Preston, C., Mahon, E., Cataldo, J.R., McPherson, J.M., A comparison of the pharmacological properties of carbohydrate remodeled recombinant and placental-derived beta-glucocerebrosidase: Implications for clinical efficacy in treatment of Gaucher disease (1999) Blood, 93, pp. 2807-2816; Grabowski, G.A., Leslie, N., Wenstrup, R., Enzyme therapy for Gaucher disease: The first 5 years (1998) Blood Rev., 12 (2), pp. 115-133; Samuel, R., Katz, K., Papapoulos, S.E., Yosipovitch, Z., Zaizov, R., Liberman, U.A., Aminohydroxy propylidene bisphosphonate (APD) treatment improves the clinical skeletal manifestations of Gaucher's disease (1994) Pediatrics, 94 (3), pp. 385-389; Shiffmann, R., Mankin, H., Dambrosia, J.M., Xavier, R.J., Kreps, C., Hills, S.C., Barton, N.W., Rosenthal, D.I., Decreased bone density in splenectomized Gaucher patients receiving enzyme replacement therapy (2002) Blood Cells Mol. Dis., 28, pp. 288-296; (1993) Iodine-125, a Guide to Radioiodination, p. 64. , Amersham Life Science; Barrias, C.C., Martins, M.C.L., Sá Miranda, M.C., Barbosa, M.A., Adsorption of a therapeutic enzyme to self-assembled monolayers: Effect of surface chemistry and solution pH on the amount and activity of adsorbed enzyme (2005) Biomaterials, 26, pp. 2695-2704; Laemmli, U.K., (1970) Nature, 227, pp. 680-685; Sá Miranda, M.C., Aerts, J.M., Pinto, R., Fontes, A., Lacerda, L.W., Van Weely, S., Barranger, J., Tager, J.M., Activity of glucocerebrosidase in extracts of different cell types from type 1 Gaucher disease patients (1990) Clin. Genet., 38, pp. 218-227; Barrias, C.C., Lamghari, M., Granja, P.L., Sá Miranda, C., Barbosa, M.A., Biological evaluation of calcium alginate microspheres as a vehicle for the localised delivery of a therapeutic enzyme (2005) J. Biomed. Mater. Res.; Barrias, C.C., Ribeiro, C.C., Lamghari, M., Sá Miranda, C., Barbosa, M.A., Proliferation, activity, and osteogenic differentiation of bone marrow stromal cells cultured on calcium titanium phosphate microspheres (2005) J. Biomed. Mater. Res., 72 A (1), pp. 57-66; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Calcium phosphate-alginate microspheres as enzyme delivery matrices (2004) Biomaterials, 25 (18), pp. 4363-4373; Das, P.K., Murray, G.J., Gal, A.E., Barranger, J.A., Glucocerebrosidase deficiency and lysosomal storage of glucocerebroside induced in cultured macrophages (1987) Exp. Cell Res., 168 (2), pp. 463-474; Pelled, D., Shogomori, H., Futerman, A.H., The increased sensitivity of neurons with elevated glucocerebroside to neurotoxic agents can be reversed by imiglucerase (2000) J. Inherited Metab. Dis., 23 (2), pp. 175-184; Hanley, K., Jiang, Y., Holleran, W.M., Elias, P.M., Williams, M.L., Feingold, K.R., Glucosylceramide metabolism is regulated during normal and hormonally stimulated epidermal barrier development in the rat (1997) J. Lipid Res., 38 (3), pp. 576-584; Marshall, J., McEachern, K.A., Kyros, J.A., Nietupski, J.B., Budzinski, T., Ziegler, R.J., Yew, N.S., Cheng, S.H., Demonstration of feasibility of in vivo gene therapy for Gaucher disease using a chemically induced mouse model (2002) Mol. Ther., 6 (2), pp. 179-189; Mistry, P.K., Wraight, E.P., Cox, T.M., Therapeutic delivery of proteins to macrophages: Implications for treatment of Gaucher's disease (1996) Lancet, 348 (9041), pp. 1555-1559; Xu, Y.H., Ponce, E., Sun, Y., Leonova, T., Bove, K., Witte, D., Grabowski, G.A., Turnover and distribution of intravenously administered mannose-terminated human acid beta-glucosidase in murine and human tissues (1996) Pediatr. Res., 39 (2), pp. 313-322; Beutler, E., Kuhl, W., Vaughan, L.M., Failure of alglucerase infused into Gaucher disease patients to localize in marrow macrophages (1995) Mol. Med., 1, pp. 320-324; Sato, Y., Beutler, E., Binding, internalization, and degradation of mannose-terminated glucocerebrosidase by macrophages (1993) J. Clin. Invest., 91, pp. 1909-1917; Schueler, U., Kaneski, C., Murray, G., Sandhoff, K., Brady, R.O., Uptake of mannose-terminal glucocerebrosidase in cultured human cholinergic and dopaminergic neuron cell lines (2002) Neurochem. Res., 27 (4), pp. 325-330; Furbish, F.S., Steer, C.J., Barranger, J.A., Jones, E.A., Brady, R.O., The uptake of native and desialylated glucocerebrosidase by rat hepatocytes and Kupffer cells (1978) Biochem. Biophys. Res. Commun., 81, pp. 1047-1053; Furbish, F.S., Steer, C.J., Krett, N.L., Barranger, J.A., Uptake and distribution of placental glucocerebrosidase in rat hepatic cells and effects of sequential deglycosylation (1981) Biochim. Biophys. Acta, 673, pp. 425-434; East, L., Isacke, C.M., The mannose receptor family (2002) Biochim. Biophys. Acta., 1572, pp. 364-386; East, L., Rushton, S., Taylor, M.E., Isack, C.M., Characterization of sugar binding by the mannose receptor family member, Endo180 (2002) J. Biol. Chem., 277 (52), pp. 50469-50475; Engelholm, L.H., Nielsen, B.S., Netzel-Arnett, S., Solberg, H., Chen, X.D., Lopez Garcia, J.M., Lopez-Otin, C., Bugge, T.H., The urokinase plasminogen activator receptor-associated protein/endo180 is coexpressed with its interaction partners urokinase plasminogen activator receptor and matrix metalloprotease-13 during osteogenesis (2001) Lab. Invest., 81, pp. 1403-1414; Bailey, L., Wienke, D., Howard, M., Knauper, V., Isacke, C.M., Murphy, G., Investigation of the role of Endo180/urokinase-type plasminogen activator receptor-associated protein as a collagenase 3 (matrix metalloproteinase 13) receptor (2002) Biochem. J., 1 (363 PART 1), pp. 67-72
Keywords: article; Cell culture; cell extract; Cells, Cultured; conduritol b epoxide; controlled study; drug activity; drug uptake; enzyme activity; enzyme antibody; Enzyme inhibition; Enzyme uptake; epoxide; Gaucher disease; Glucocerebrosidase; Glucosylceramidase; human; human cell; Humans; imiglucerase; Inositol; internalization; iodine 125; isotope labeling; mannose receptor; osteoblast; Osteoblasts; priority journal; Recombinant Proteins; unclassified drug; Western blotting

Segmentation of ultrasonic images of the carotid - Rocha, R.; Campilho, A.; Silva, J. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2005)
A new algorithm for an effective and automatic segmentation of the carotid wall in ultrasonic images is proposed. It combines the speed of thresholding algorithms with the accuracy, flexibility and robustness of a successful geometric active contour model which incorporates an optimal image segmentation model in a level set framework. Due to the multiphase nature of these images, a sequential minimum cross entropy thresholding is used to get a first approximation of the segments, reducing the problem to a two phase segmentation. This thresholding solution is then used as a starting point for a two phase piecewise constant version of a geometric active contour model to reduce noise, smooth contours, improve their position accuracy and close eventual gaps in the carotid wall. © Springer-Verlag Berlin Heidelberg 2005.
Conference code: 67124Export Date: 21 November 2012Source: Scopusdoi: 10.1007/11559573_115Language of Original Document: EnglishCorrespondence Address: Rocha, R.; INEB - Instituto de Engenharia Biomédica, Laboratório de Sinai e Imagem Biomédica, Porto, PortugalReferences: Gee, A., Prager, R., Treece, G., Berman, L., Engineering a freehand 3D ultrasound system (2003) Pattern Recogn. Lett., 24, pp. 757-777;Sonka, M., Liang, W., Stefancik, R., Stolpen, A., (2000) Handbook of Medical Imaging: Medical Image Processing and Analysis, 2. , SPIE; Christodoulou, C.I., Pattichis, C.S., Pantziaris, M., Nicolaides, A., Texture based classification of atherosclerotic carotid plaques (2003) IEEE Trans. Med. Imaging, 22, pp. 902-912; Barratt, D., Ariff, B., Humphries, K., Thom, S., Hughes, A., Reconstruction and quantification of the carotid artery bifurcation from 3-d ultrasound images (2004) IEEE Trans. Med. Imaging, 23, pp. 567-583; Li, C., Lee, C., Minimum cross entropy thresholding (1993) Pattern Recogn, 26, pp. 617-625; Brink, A., Pendock, N., Minimum cross-entropy threshold selection (1996) Pattern Recogn., 29, pp. 179-188; Chan, T., Vese, L., Active contours without edges (2001) IEEE Trans. on Image Processing, 10, pp. 266-277; Vese, L.A., Chan, T.F., A multiphase level set framework for image segmentation using the Mumford and Shah model (2002) Int. J. Comput. Vision, 50, pp. 271-293; Touboul, P., Prati, P., Abd, V., Adrai, P.Y.S., Thibout, E., Ducimetiere, P., Use of monitoring software to improve the measurement of carotid wall thickness by B-mode imaging (1992) J. Hypertension, 10, pp. 37-41; Liang, Q., Wendelhag, I., Wikstrand, J., Gustavsson, T., A multiscale dynamic programming procedure for boundary detection in ultrasound artery images (2000) IEEE Trans. Med. Imaging, 19, pp. 127-142; Schmidt-Trucksass, A., Cheng, D., Sandrock, M., Schulte-Monting, J., Rauramaa, R., Huonker, M., Burkhardt, H., Computerized analysing system using the active contour in ultrasound measurement of carotid artery intima-media thickness (2001) Clinical Physiology, 5, pp. 561-569; Cheng, D., Schmidt-Trucksass, A., Cheng, K., Sandrock, M., Pu, Q., Burkhardt, H., Automatic detection of the intimal and the adventitial layers of the common carotid artery wall in ultrasound B-mode images using snakes (1999) International Conference on Image Analysis and Processing, pp. 452-457. , B. Werner; Cheng, D., Schmidt-Trucksass, A., Cheng, K., Burkhardt, H., Using snakes to detect the intimal and adventitial layers of the common carotid artery wall in sonographic images (2002) Computer Methods and Programs in Biomedicine, 67, pp. 27-37; Baillard, C., Barillot, C., Bouthemy, P., Robust adaptive segmentation of 3D medical images with level sets (2000) Technical Report, , IRISA, Campus Universitaire de Beaulieu, Prance; Tsai, A., Yezzi III, A.J., W., W.M., Tempany, C., Tucker, D., Fan, A., Grimson, W.E.L., Willsky, A.S., A shape-based approach to the segmentation of medical imagery using level sets (2003) IEEE Trans. Med. Imaging, 22, pp. 137-154; Perona, P., Malik, J., Scale-space and edge detection using anisotropic diffusion (1990) IEEE Trans. Pattern Anal. Mach. Intell., 12, pp. 629-639; Sethian, J.A., (1999) Level Set Methods and Fast Marching Methods, , Cambridge University Press; Osher, S., Fedkiw, R., (2003) Level Set Methods and Dynamic Implicit Surfaces, , Springer-Verlag. New York; Mumford, D., Shah, J., Optimal approximations by piecewise smooth functions and associated variational problems (1989) Communications on Pure and Applied Mathematics, 42, pp. 577-685; Gao, S., Bui, T.D., Image segmentation and selective smoothing by using the Mumford-Shah model (2005) IEEE Trans. on Image Processing, , To be published in
Keywords: Active contour model; Algorithms; Approximation theory; Carotid wall; Image segmentation; Image segmentation model; Mathematical models; Optimization; Ultrasonic imaging

TiO 2 type influences fibronectin adsorption - Sousa, S.R.; Moradas-Ferreira, P.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2005)
Human fibronectin (FN) plays a key role in the biointegration of implants as the success depends on adsorption of proteins like FN [1]. Indeed FN can be an intermediary between the biomaterial surface and cells. The adsorption of human fibronectin (FN) on commercially pure titanium with a titanium oxide layer formed in a H 2O 2 solution (TiO 2 cp) and TiO 2 sputtered on Si (TiO 2 sp) was studied. Adsorption isotherms and the work of adhesion were assessed by wettability studies, X-ray photoelectron spectroscopy (XPS), and by radiolabelling of FN with 125I, 125I-FN. Exchangeability of bound FN by free FN, was also evaluated by the radiolabelling technique. Contact angle determinations have shown that FN displays higher affinity for the TiO 2 cp surface than for the TiO 2 sp. As expected from the surface free energy values, the work of adhesion of FN is higher for the TiO 2 cp substrate, the more hydrophilic one, and lower for the TiO 2 sp substrate, the more hydrophobic one. The adsorption isotherms were evaluated by two different techniques: radiolabelling of FN ( 125I-FN) and XPS. TiO 2 cp adsorbs more FN than the TiO 2 sp surfaces as shown by the radiolabelling data. FN molecules are also more strongly attached to the former surface as indicated by the work of adhesion and by the exchangeability studies. Results using 125I-FN also suggests that FN adsorbs as a multilayer for FN concentrations in solution higher than 100 μg/mL. © 2005 Springer Science + Business Media, Inc.
Cited By (since 1996): 28Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-005-4725-4Language of Original Document: EnglishCorrespondence Address: Sousa, S.R.; INEB, Instituto de Engenharia Biomédica, Lab. Biomateriais, R. do Campo Alegre, 823, 4150-180 Porto, Portugal; email: ssousa@ibmc.up.ptChemicals/CAS: fibronectin, 86088-83-7; titanium dioxide, 1317-70-0, 1317-80-2, 13463-67-7, 51745-87-0; titanium, 7440-32-6; hydrogen peroxide, 7722-84-1; iodine 125, 14158-31-7, 22822-81-7; Fibronectins; Solutions; titanium dioxide, 13463-67-7; Titanium, 7440-32-6References: Horbett, T.A., (1994) Colloids and Surfaces B: Biointerfaces, 2, p. 225;Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., (2005) J Biomed Mater Res., 75 A, p. 387; Johnson, K.J., Sage, H., Briscoe, G., Erickson, H.P., (1999) J. Biol. Chem., 274, p. 15473; Bergkvist, M., Carlsson, J., Oscarsson, S., (2003) J. Biomed. Mater. Res. Part A., 64 A, p. 349; Ugarova, T.P., Zamarron, C., Veklich, Y., Bowditch, R.D., Ginsberg, M.H., Weisel, J.W., Plow, E.F., (1995) Biochemistry, 34, p. 4457; Sukenik, C.N., Balachander, N., Culp, L.A., Lewandowska, K., Merritt, K., (1990) J. Biomed. Mater. Res., 24, p. 1307; Sousa, S.R., Moradas- Ferreira, P., Melo, L.V., Saramago, B., Barbosa, M.A., (2004) Langmuir, 20, p. 9745; Gehanno, V., Freitas, P.P., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Soares, J.C., Silva, M.F., (1999) IEEE Trans. Magn., 35, p. 4361; (2003) Iodine-125, A Guide to Radioiodination Techniques - Amersham Life Science, p. 64. , Amersham International plc, Amersham Place, Little Chalfont, Bucks, HP7 9NA, England, 199; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., (2001) J. Biomed. Mater. Res., 55, p. 45; Yu, X.J., Brash, J.L., (1993) Test Procedures for the Blood Compatibility of Biomaterials, Dordrecht, p. 287. , edited by S. Dawids (Kluwer Academic Publishers, Dordrecht); Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., (1985) Analytical Biochemistry, 150, p. 76; Lindberg, B., Maripuu, R., Siegbahn, K., Larsson, R., Golander, C.G., Eriksson, J.C., (1983) J. Colloid Interface Sci., 95, p. 308; Auditore, A., Satriano, C., Coscia, U., Ambrosone, G., Parisi, V., Marletta, G., (2002) Biomolecular Engineering, 19, p. 85; Miller, R., Treppo, S., Voigt, A., Zingg, W., Neumann, A.W., (1993) Colloids and Surfaces, 69, p. 203; Serro, A.P.V., Fernandes, A.C., Saramago, B.D.V., (1997) Colloids and Surfaces A-Physicochemical and Engineering Aspects, 125, p. 209; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., (1997) Langmuir, 13, p. 3404; Matsuura, T., Hosokawa, R., Okamoto, K., Kimoto, T., Akagawa, Y., (2000) Biomaterials, 21, p. 1121; Ferraz, M.P., Monteiro, F.J., Serro, A.P., Saramago, B., Gibson, I.R., Santos, J.D., (2001) Biomaterials, 22, p. 3105; Do Serro, A., Fernandes, A.C., Saramago, B.D.V., Norde, W., (1999) J. Biomed. Mater. Res., 46, p. 376; Norde, W., Anusiem, A.C.I., (1992) Colloids and Surfaces, 66, p. 73; Rouxhet, L., Duhoux, F., Borecky, O., Legras, R., Schneider, Y.J., (1998) Journal of Biomaterials Science-Polymer Edition, 9, p. 1279; Norde, W., (1986) Advances in Colloid and Interface Science, 25, p. 267; Tamada, Y., Ikada, Y., (1993) J. Colloid Interface Sci., 155, p. 334
Keywords: Adsorption; adsorption kinetics; article; binding affinity; Biointegration; Biomaterials; Cells; chemistry; conference paper; Contact angles; Fibronectin; Fibronectins; human; Human fibronectin (FN); Humans; hydrogen peroxide; hydrophilicity; hydrophobicity; Implants (surgical); iodine 125; isotherm; Isotherms; isotope labeling; physical chemistry; priority journal; protein binding; Proteins; Radiolabelling; solution and solubility; Solutions; surface property; Titanium; Titanium dioxide; wettability; X ray photoelectron spectroscopy

Automatic lane and band detection in images of thin layer chromatography - Sousa, A.V.; Aguiar, R.; Mendonca, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2004)
This work aims at developing an automatic method for the analysis of TLC images for measuring a set of features that can be used for the characterization of the distinctive patterns that result from the separation of oligosaccharides contained in human urine. This paper describes the methods developed for the automatic detection of the lanes contained in TLC images, and for the automatic separation of bands for each detected lane. The extraction of quantitative information related with each band was accomplished with two methods: the EM expectation-maximization and nonlinear least squares trustregion algorithms. The results of these methods, as well as additional quantitative information related with each band, are also presented. © Springer-Verlag 2004.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Sousa, A.V.; Institute de Engenharia Biomédica, Rua Roberto Prias, 4200-465 Porto, Portugal; email: ats@isep.ipp.ptReferences: Sewell, A., (1991) Urinary Oligosaccharides. Techniques in Diagnostic Human Biochemical Genetics, pp. 219-231. , Willey-Liss, Inc;Thomas, G., Disorders of Glycoprotein Degradation. α-Mannosidosis, β-Mannosidosis, Fucosidosis and Sialidosis, , Disorders of Glycoprotein Degradation (Chap. 140); Starr, C., Masada, R., Hague, C., Klock, J., Fluorophore-assisted Carbohydrate Electrophoresis in the Separation, Analysis, and Sequencing of Carbohydrates (1996) Journal of Chromatography A, 720, pp. 295-321; Klein, A., Lebreton, A., Lemoine, J., Périni, J., Roussel, P., Michalski, J., Identification of Urinary Oligosaccharides by Matrix-assisted Laser Desorption Ionization Time-of-flight Mass Spectrometry (1998) Clinical Chemistry, 44 (12), pp. 2422-2428; Dempster, A., Laird, N., Rubin, D., Maximum Likelihood from Incomplete Data via the em Algorithm (1977) Journal of the Royal Statistical Society, B, 39 (1), pp. 1-38; Schwedt, G., The Essential Guide to Analytical Chemistry, , John Wiley & Sons; Dennis, J., Nonlinear Least-squares, State of the Art in Numerical Analysis, , D. Jacobs Academic Press; Byrd, R., Schnabel, R., Shultz, G., Approximate Solution of the Trust Region Problem by Minimization over Two-Dimensional Subspaces (1988) Mathematical Programming, 40, pp. 247-263; Branch, M., Coleman, T., Li, Y., A Subspace, Interior, and Conjugate Gradient Method for Large-Scale Bound-Constrained Minimization Problems (1999) SIAM SISC, 21 (1), pp. 1-23; Nabney, I., Netlab Algorithms for Pattern Recognition (2003) Advances in Pattern Recognition, , Springer; Marques, J., Reconhecimento de Padrões, , Métodos Estatisticos e Neuronais, IST-Press; Machado, A., Campos, M., Siqueira, A., Carvalho, O., (1997) An Iterative Algorithm for Segmenting Lanes in Gel Electrophoresis Images;

Biological Activity of Two Glass Ceramics in the Meta- and Pyrophosphate Region: A Comparative Study - Dias, A.G.; Costa, M.A.; Lopes, M.A.; Santos, J.D.; Fernandas, M.H. (Key Engineering MaterialsKey Eng Mat, 2004)
Based upon the CaO-P 2O 5 glass system, two glass ceramics were prepared in the metaand pyrophosphate regions. The present work describes preliminary results concerning the biological activity of MK5B (45CaO-45P 2O 5-5MgO-5K20, in mol %) and MT13B (45CaO-37P 2O 55-5MgO-13TiO 2, in mol %) using MG63 osteoblast-like cells. Both materials supported cell growth and proliferation which increased with the incubation time. However, cell growth was significantly lower on seeded MK5B samples. SEM observation showed that cell adhesion and spreading were hampered on this material. Evident degradation of the material surface was observed with simultaneous cell proliferation and material precipitation. By contrast, MT13B presented a relatively stable surface throughout the culture time. Results suggest that the in vitro biological behaviour of MK5B and MT13B is related with differences in the degradation rates of the two materials during the culture time.
Conference code: 62053Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Dias, A.G.; Faculdade de Engenharia, Universidade do Porto, DEMM, Rua Dr. Roberta Frias, 4200 Porto, PortugalReferences: Dias, A.G., Lopes, M.A., Gibson, I., Santos, J.D., J. Non-Crystal. Solids, , in press;Dias, A.G., Lopes, M.A., Tsuru, K., Hayakawa, S., Santos, J.D., Osaka, A., Physiscs and Chemistry of Glasses, , in press; Dias, A.G., Lopes, M.A., Santos, J.D., Advance Materials Science, , in press; Rykke, M., Rolla, G., Sonju, T., (1988) Scand. J. Dent. Res., 96, pp. 517-522
Keywords: Adhesion; Biodegradable glass ceramics; Biodegradation; Bone; cell proliferation; Cells; Crystallization; Degradation; Glass ceramics; incubation time; MG63 osteoblast-like cells; Scanning electron microscopy; X ray diffraction

Bonelike®/PLGA hybrid materials for bone regeneration: In vivo evaluation - Oliveira, J.M.; Kawai, T.; Lopes, M.A.; Ohtsuki, C.; Santos, J.D.; Afonso, A. (Materials Science ForumMater Sci Forum, 2004)
The biocompatibility and osteoconductive potential of Bonelike® and Bonelike®/PLGA hybrid materials were evaluated through subcutaneous and tibiae implantations for a 4 week period. Qualitative histology was performed to evaluate new bone formation and characterise bone-implant interface and results showed that Bonelike®/PLGA hybrid materials promote extensive bone growth. After the 4 week implantation period, Bonelike® resorption was recognized, which may be due to the presence of resorbable β and α-tricalcium phosphate phases.
Conference code: 63332Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: MSFOELanguage of Original Document: EnglishCorrespondence Address: Oliveira, J.M.; Inst. de Engenharia Biomédica, Lab. de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jmolive@fe.up.ptReferences: Praemer, A., Furner, S., Rice, D.P., (1992) Am. Acad. Orthop. Surg., p. 1;Glowacki, J., Mulliken, J.B., (1985) Clin. Plast. Surg., 12, p. 233; Buck, B.E., Malinin, T.I., Brown, M.D., (1989) Clin. Orthop., 36, p. 129; Sepulveda, P., Bressiani, A.H., Bressiani, J.C., Mesenguer, L., König Jr., B., (2002) J. Biomed. Mater. Res. Vol., 62, p. 587; Glimcher, M.J., (1987) Instr. Course Lect., 36, p. 46; Yakamuro, T., Hench, L.L., Wilson, J., (1990) CRC Handbook of Bioactive Ceramics, 2, pp. 245-252; Klemm, K.W., (1993) Clin. Orthop. & Rel. Res., 295, pp. 63-76; Agrawal, C.M., Ray, R.B., (2001) J. Biomed. Mater. Res., 55, p. 141; Santos, J.D., Campbell, J.K., Winton, G.H., (2000), European Patent N° W00068164Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463
Keywords: Bacteria; Biodegradation; Bone; Bonelike resorption; Bonelike®; Histological studies; histology; Hybrid materials; hydroxyapatite; In vivo; physiology; PLGA; Polymers; Surgery; Tissue

CaO-P 2O 5 Glass-Hydroxyapatite Thin Films Obtained by Laser Ablation: Characterisation and In Vitro Bioactivity Evaluation - Ferraz, M.P.; Monteiro, F.J.; Gião, D.; Leon, B.; Gonzalez, P.; Liste, S.; Serra, J.; Arias, J.; Perez-Amor, M. (Key Engineering MaterialsKey Eng Mat, 2004)
Hydroxyapatite (HA) coatings have been applied to improve adhesion of non-cemented implants to host bone. Plasma spraying is the most common technique leading to thick calcium phosphate films (>120μm). Pulse laser deposition (PLD), is a possible alternative method to obtain thin (<10 μm), well adherent hydroxyapatite (HA) films. Similarly to synthetic HA, biological apatites contain Ca 2+, PO 4 3- and OH
Conference code: 62053Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Ferraz, M.P.; Inst. de Engenharia Biomédica, Laboratório de Biomateriais, Rua Campo Alegre 823, 4150-180 Porto, Portugal; email: mpferraz@ufp.ptReferences: Arias, J.L., (1997) J Mater. Sci. Mater. Med., 8, pp. 873-876;Peraire, C., (1997) 13 th European Conference on Biomaterials, p. 75. , Göteborg, Sweden, 4-7 Sept; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J Biomed Mater Res, 45, p. 373; Ferraz, M.P., Fernandes, M.H., Trigo-Cabral, A., Santos, J.D., Monteiro, F.J., (1999) J. Mat Sci: Mat. Med, 10 (9), p. 567
Keywords: 2O; 5 glass; Adhesion; Bioactivity; Bone; Calcium Compounds; CaO-P; Coatings; Deposition; Energy dispersive spectroscopy; Homogeneous mixtures; Hydroxylapatite thin films; Implants (surgical); In vitro bioactivity; Laser ablation; Plasma spraying; Scanning electron microscopy; Thin films; X ray diffraction

A comparative study of CaO-P 2O 5-SiO 2 gels prepared by a sol-gel method - Hussain, N.S.; Lopes, M.A.; Santos, J.D. (Materials Chemistry and PhysicsMater Chem Phys, 2004)
This paper reports on the results concerning the preparation and systematic analysis of CaO-P 2O 5-SiO 2 gels by a sol-gel process. The concentration of SiO 2 influence on these gels and found the results are very encouraging. Studies have revealed that the concentration of SiO 2 has a marginal influence on the phase formation of these gels. It has appreciable changes from less configured particles at lower values of concentration, with an ultimate growth in a highly crystalline fibrous nature at higher concentrations of SiO 2. The authors have examined the changes in the morphology of these gels by a scanning electron microscope with an energy dispersive analyser (SEM/EDS techniques) and also from the profiles of Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) spectral data and reported the crystalline product containing the fibrous β-Ca(PO 3) 2 as a major phase in the materials studied. © 2004 Elsevier B.V. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: MCHPDdoi: 10.1016/j.matchemphys.2004.06.015Language of Original Document: EnglishCorrespondence Address: Hussain, N.S.; DEMM, Faculty of Engineering, University of Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: sooraj@fe.up.ptReferences: Hench, L.L., (1991) J. Am. Ceram. Soc., 74, p. 1487;Hench, L.L., Wilson, J., (1993) An Introduction to Bioceramics, , World Scientific, Singapore; Ohtsuki, C., Kokubo, T., Yamamuro, T., (1992) J. Non-cryst. Solids, 143, p. 84; Kokubo, T., Yoshihara, S., Nishimura, N., Yamamuro, T., Nakamura, T., (1991) J. Am. Ceram. Soc., 74, p. 1739; Ota, Y., Iwashita, T., Kasuga, T., Abe, Y., Seki, A., (2001) Key Eng. Mater., 192-195, p. 421; Kasuga, T., Ota, Y., Nogami, M., Abe, Y., (1996) Phos. Res. Bull., 6, p. 75; Ota, Y., Kasuga, T., Abe, Y., (1997) J. Am. Ceram. Soc., 80 (1), p. 225; Zhang, Y., Santos, J.D., (2000) J. Non-cryst. Solids, 227, p. 14; Yoldas, B.E., (1975) Ceram. Bull., 54, p. 286; Thomas, I.M., (1988) Sol-gel Technology for Thin Films, Fibres, Preforms, Electronics and Specialty Shapes, p. 2. , L.C. Klein (Ed.), Noyes, NJ; Brinker, C.J., Scherer, G.W., (1990) Sol-gel Science: The Physics and Chemistry of Sol-gel Processing, , Academic Press, New York; Hench, L.L., West, J.K., (1990) Chem. Rev., 90, p. 33; Hench, L.L., (1998) Sol-gel Silica: Properties, Processing and Technology Transfer, , Noyes, New Jersey; Salinas, A.J., Martin, A.I., Vallet-Regí, M., (2002) J. Biomed. Mater. Res., 61 (4), p. 524; Laczka, M., Cholewa, K., Lazca-Osyczka, A., (1997) J. Alloys Comp., 248, p. 42; Roman, J., Padilla, S., Vallet-Regí, M., (2003) Chem. Mater., 15 (3), p. 798; Li, R., Clark, A.E., Hench, L.L., (1991) J. Appl. Biomater., 2, p. 231; Rámila, A., Vallet-Regí, M., (2001) Biomaterials, 22, p. 2301; Balas, F., Arcos, D., Pérez-Pariente, J., Vallet-Regí, M., (2001) J. Mater. Res., 16 (5), p. 1345; Peitl, O., Zanotto, E.D., Hench, L.L., (2001) J. Non-cryst. Solids, 292, p. 115; Casu, M., Casula, M.F., Corrias, A., Pachina, G., (2003) J. Non-cryst. Solids, 315, p. 97; Motke, S.G., Yawale, S.P., Yawale, S.S., (2002) Bull. Mater. Sci., 25 (1), p. 75; Méndez-Vivar, J., Mendoza-Bandala, A., (2000) J. Non-cryst. Solids, 261, p. 127; Popa, M., Calderon-Moreno, J.M., Popescu, L., Kakihana, M., Torecillas, R., (2002) J. Non-cryst. Solids, 297, p. 290; Sooraj Hussain, N., Prabhakara Reddy, Y., Buddhudu, S., (2002) Spectrosc. Lett., 35 (2), p. 275; Mackenzie, J.D., (1986) Science of Ceramic Chemical Processing, p. 112. , L.L. Hench, D.R. Ulrich (Eds.), Wiley/Interscience; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , Jpn. Assoc. Apatite Sci. (JASS)
Keywords: Bioactivity; Calcium Compounds; Calcium phosphosilicates; Fourier transform infrared spectroscopy; Gels; morphology; Phase composition; Phase formation; Phosphorus Compounds; Scanning electron microscopy; Silica; Sol-gel process; Sol-gels; X ray diffraction analysis

Crystallisation studies of biodegradable CaO-P 2O 5 glass with MgO and TiO 2 for bone regeneration applications - Dias, A.G.; Tsuru, K.; Hayakawa, S.; Lopes, M.A.; Santos, J.D.; Osaka, A. (Glass TechnologyGlass Technol, 2004)
CaO-P 2O 5 glass ceramics with small additions of MgO and TiO 2 were prepared in the ortho and pyrophosphate regions by powder sintering and crystallisation through heat treatment at different temperatures determined from differential thermal analysis (DTA). The glass ceramics were analysed by x-ray diffraction (XRD) and it was observed that α- and β-Ca 2P 2O 7 were the first phases to precipitate in the parent glass matrix at a temperature of 681°C, followed by CaTi 4(PO 4) 6 and TiP 2O 7 at temperatures between 703 and 725°C. The β-Ca 2P 2O 7 and CaTi 4(PO 4) 6 phases are usually considered as biocompatible and bioactive and, therefore, these glass ceramics seem to show good potential for bone regeneration applications.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: GLSTALanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB, Inst. de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Siligardi, C., D'Arrigo, M.C., Leonelli, C., Sintering behavior of glass ceramics frits (2000) Am. Ceram. Soc. Bull., pp. 88-92;Clarck, T.J., Reed, J.S., Kinetic processes involved in the sintering and crystallization of glass powders (1986) J. Am. Ceram. Soc., 69 (11), pp. 837-846; Karmakar, B., Kundu, P., Jana, S., Dwivedi, R.N., Crystallization kinetics and mechanism of low-expansion lithium aluminosilicate glass-ceramics by dilatometry (2002) J. Am. Ceram. Soc., 85 (10), pp. 2572-2577; Zhang, Y., Santos, J.D., Crystallization and microstructure analysis of calcium phosphate-based glass ceramics for biomedical applications (2000) J. Non-cryst. Solids, 272 (1), pp. 14-21; Ryu, H.-S., Youn, H.-J., Chang, B.-S., Lee, C.-K., Chung, S.-S., An improvement in sintering property of β-tricalcium phosphate by addition of calcium pyrophosphate (2002) Biomaterials, 23, pp. 909-914; Kitsugi, T., Yamamuro, T., Nakamura, T., Ota, M., Transmission electron microscopy observations at the interface of bone and four types of calcium phosphate ceramics with different calcium/phosphorous molar ratios (1995) Biomaterials, 16, pp. 1101-1107
Keywords: Biodegradation; Bone Regeneration; Crystallization; Differential thermal analysis; Diffractometers; Glass ceramics; Glass matrix; Glass transition; Laser diffraction; Lime; Magnesia; methanol; Monochromators; Precipitation (chemical); Temperature scanning; Titanium dioxide; X ray powder diffraction

Effect of the Solvents on the Solution Mixture Derived Polylactide/hydroxyapatite Composites - Li, Y.; Weng, W.; Cheng, K.; Du, P.; Shen, G.; Han, G.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2004)
Polylactide/hydroxyapatite composites were prepared by a solution mixture method. Chloroform and tetrahydrofuran were used as solvents. The effect of the solvents on the polylactide/hydroxyapatite composites was investigated by TEM, mechanical properties, sedimentation time and UV-Vis transmission spectra. The results indicate that the polylactide/hydroxyapatite prepared using tetrahydrofuran as solvent has better dispersion of the hydroxyapatite filler in the matrix and larger bend strength than the one using chloroform as solvent. This is ascribed to the proper interaction between the solvent and hydroxyapatite filler.
Conference code: 62053Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Weng, W.; Dept. of Mat. Sci. and Engineering, Zhejiang University, Hangzhou 310027, China; email: wengwj@zju.edu.cnReferences: Hench, L.L., (1998) Journal of American Ceramic Society, 81, p. 1705;Wang, M., (2003) Biomaterials, 24, p. 2133; Hao, J., Yuan, M., Deng, X., (2001) Biomaterials, 22, p. 2867; Ignjatovic, N., Tomic, S., Dakic, M., Miljkovic, M., Plavsic, M., Uskokovic, D., (1999) Biomaterials, 20, p. 809; Misra, D.N., (1988) Langmuir, 4, p. 953; Dean, J.A., (1999) Lange's Handbook of Chemistry (15th Edition), , McGraw-HILL, INC. New York
Keywords: Bend strength; Composite; Composite materials; dispersion; Dispersions; Fillers; Heat treatment; Hydroxvapatite; hydroxyapatite; Polarity; polylactide; Sedimentation; Solutions; Solvent; Solvents; transmission electron microscopy; Ultraviolet radiation

Effects of some variables on R.F. Magnetron Sputtered Hydroxyapatite Coatings on Titanium - Silva, R.A.; Sousa, M.; Monteiro, F.J.; Barral, R.; Santos, J.D.; Lopes, M.A. (Key Engineering MaterialsKey Eng Mat, 2004)
RF sputtering may be used to produce thin, well adherent bioactive coatings with long term stability to ensure contact with bone tissue. RF Sputtered Hydroxyapatite (HA) coatings were produced onto Ti at 200 and 150 W. S.E.M. analysis indicated that films obtained with 200 W were thicker than those with 150 W. Significant variations were observed, depending on the location of the substrates with respect to the sample holder in the sputtering chamber, with thickness ranging from 1.8 to 3.2 μm. EDS analysis of 200 W films revealed the presence of Ca and P, in ratios typical of HA. XPS of thinner films obtained at 150 W, showed Ca and P, but also some carbonate probably partially substituting OH. Anodic polarisation curves of samples coated at 200 W and 150 W and for different sputtering times, compared to Ti substrate, indicate that HA films were protective and that the degree of protection increased with film thickness, i.e., with power intensity and time of deposition.
Conference code: 62053Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Silva, R.A.; Inst. Sup. de Engenharia do Porto, Rua Dr. Antonio Bernardino A., 431, 4200-072 Porto, Portugal; email: ras@isep.ipp.ptReferences: Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., (1997) Journal of Materials Science: Materials in Medicine, 8, pp. 731-736;Raynaud, S., Champion, E., Bernache-Assolant, D., Tetard, D., (1998) Journal of Materials Science: Materials in Medicine, 9, pp. 221-227; Weng, J., Liu, X., Zhang, X., De Groot, K., (1996) Journal of Biomedical Materials Research, 30, pp. 5-11; Gross, K.A., Gross, V., Berndt, C.C., (1998) Journal of the American Ceramic Society, 81 (1), pp. 106-112; Edwards, J.T., Brunski, J.B., Higuchi, (1997) Journal of Biomedical Materials Research, 36, pp. 454-468; Yang, C.Y., Lin, R.M., Wang, B.C., Lee, T.M., Chang, E., Hang, Y.S., Chen, P.Q., (1997) Journal of Biomedical Materials Research, 37, pp. 335-345; Ogiso, M., Yamamura, M., Kuo, P.T., Borgese, D., Matsumoto, T., (1998) Journal of Biomedical Materials Research, 39, pp. 364-372; Van Dijk, K., Schaeken, H.G., Wolke, J.G.C., Maree, C.H.M., Habraken, F.H.P.M., Jansen, J.A., (1995) Materials in Clinical Applications, pp. 249-256. , P. Vincenzini, (ed.); Yoshinari, M., Hayakawa, T., Wolke, J.G.C., Nemoto, K., Jansen, J.A., (1997) Journal of Biomedical Materials Research, 37, pp. 60-67; Wolke, J.G.C., De Groot, K., Jansen, J.A., (1998) Journal of Biomedical Materials Research, 39, pp. 524-530
Keywords: Bioactive coatings; Bone; Coatings; Corrosion protection; hydroxyapatite; Magnetron sputtering; Plasma spraying; Polarization; RF sputtering; Scanning electron microscopy; Sputter deposition; Sputtering chambers; Thin films; Titanium

Fabrication of alternating polycation and albumin multilayer coating onto stainless steel by electrostatic layer-by-layer adsorption - Ji, J.; Tan, Q.; Fan, D.-Z.; Sun, F.-Y.; Barbosa, M.A.; Shen, J. (Colloids and Surfaces B: BiointerfacesColloids Surf. B Biointerfaces, 2004)
Multilayer films consisting of polyethylenimine (PEI) and albumin were successfully prepared on biomedical 316L stainless steel surface via electrostatic self-assembly of the PEI and albumin. The process of electrostatic self-assembly of PEI/albumin was monitored by 125I radiolabeling, electrochemical impedance spectroscopy (EIS) and atomic force microscopy (AFM). The EIS data revealed that the multilayer coating was stable in Tris-HCl (pH 7.35) buffer solution for 21 days. 125I radiolabeling experiments indicated that less than 10% albumin was eluted by PBS in 45 days. Static platelet adhesion experiments indicated that the PEI/albumin deposited on stainless steel could resist platelet adhesion effectively. Such an easy processing and shape-independent method may have good potential for surface modification of cardiovascular devices. © 2004 Elsevier B.V. All rights reserved.
Cited By (since 1996): 17Export Date: 21 November 2012Source: ScopusCODEN: CSBBEdoi: 10.1016/j.colsurfb.2003.12.015PubMed ID: 15261073Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, Hangzhou 310027, China; email: jianji@mail.hz.zj.cnChemicals/CAS: iodine 125, 14158-31-7, 22822-81-7; polyethyleneimine, 74913-72-7; stainless steel, 12597-68-1; Albumins; Lipid Bilayers; Polyamines; polycations; Polyethyleneimine, 9002-98-6; Stainless Steel, 12597-68-1References: Thomann, U.I., Uggowitzer, P.J., (2000) Wear, 239, p. 48;Cheatham, J., (2001) Prog. Pediat. Cardiol., 14, p. 95; Donachie, M., (1998) Adv. Mater. Process, 154, p. 63; Bertrand, P., (2000) Macromol. Rapid Commun., 21, p. 319; Ulman, A., (1996) Chem. Rev., 96, p. 1533; Sano, M., Lvov, Y., Kunitake, T., (1996) Annu. Rev. Mater. Sci., 26, p. 153; Laschewsky, A., (1997) Eur. Chem. Chronicle (ECC), 2, p. 13; Decher, G., (1997) Science, 277, p. 1232; Yoo, D., Seimei, S., Michael, F.R., (1998) Macromolecules, 31, p. 4309; Picart, C., Lavalle, Ph., Hubert, P., Cuisinier, F.J.G., Decher, G., Schaaf, P., Voegel, J.-C., (2001) Langmuir, 17, p. 7414; Houska, M., Brynda, E., (1997) J. Colloid Interf. Sci., 188, p. 243; Brynda, E., Houska, M., (1996) J. Colloid Interf. Sci., 183, p. 18; Lu, C.H., Luo, C.Q., Cao, W.X., (2002) Colloids Surf. B: Biointerf., 25, p. 19; Keogh, R.J., Eaton, J.W., (1994) J. Lab. Clin. Med., 124, p. 537; Munro, M.S., (1981) Trans. Am. Soc. Artif. Intern. Organs, 27, p. 499; Brynda, E., Houska, M., (2000) Protein Architecture: Interfacing Molecular Assemblies and Immobilization, pp. 251-285. , Y. Lvov, H. Moehwald (Eds.), Marcel Dekker, New York; Keogh, J.R., Velander, F.F., Eaton, W., (1992) J. Biomed. Mater. Res., 26, p. 441; Ji, J., Feng, L., Barbosa, M.A., (2001) Biomaterials, 22, p. 3015; Lopez, G.P., Ratner, B.D., Tidwell, C.D., Haycox, C.L., Rapoza, R.J., Horbett, T.A., (1992) J. Biomed. Mater. Res., 26, p. 415; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of Biocompatibility Tests, 2, pp. 183-214. , D.F. Williams (Ed.), CRC Press, Harcover; Cheng, Z., Cheng, L., Dong, S., Yang, X., (2001) J. Electrochem. Soc., 148, p. 227; Lima, J., (2001) J. Biomed. Mater. Res., 55, p. 45; Iodine-125, a Guide to Radioiodination Techniques (1993) Amersham Life Sci., p. 64; Takahara, A., Jo, N.J., Kajiyama, T., (1989) J. Biomater. Sci. Polym. Ed., 1, p. 17; Haynes, C.A., Norde, W., (1994) Colloids Surf. B: Biointerf., 2, p. 517; Ladam, G., Gergely, C., Senger, B., Decher, G., Voegel, J.C., Schaaf, P., Cuisinier, F.J.G., (2000) Biomacromolecules, 1, p. 674; Ladam, G., Schaaf, P., Cuisinier, F.J.G., Decher, G., Voegel, J.C., (2001) Langmuir, 17, p. 878; Bertrand, P., Jonas, A., Laschewsky, A., Legras, R., (2000) Macromol. Rapid Commun., 21, p. 319
Keywords: Adhesion; Adsorption; Albumin; Albumins; article; Atomic force microscopy; Cardiovascular devices; Chemical modification; Coatings; Electric Impedance; Electric Potential; Electrochemical impedance spectroscopy; electrochemistry; Electrons; Electrostatics; film coating; iodine 125; isotope labeling; Layer-by-layer; Lipid Bilayers; Microscopy, Atomic Force; Multilayers; Nonthrombogenic; pH effects; Platelet Adhesiveness; Polyamines; polycation; Polycations; Polyethyleneimine; priority journal; Proteins; Self assembly; Spectroscopy; Spectrum Analysis; Stainless steel; Surface modification; Surface Properties; surface property; Surface treatment; thrombocyte adhesion

Fabrication of alternating polycation and albumin multilayer coating by electrostatic layer-by-layer adsorption - Ji, J.; Tan, Q.; Fan, D.-Z.; Sun, Y.-F.; Barbosa, M.A.; Shen, J. (Journal of Materials ScienceJ Mater Sci, 2004)
The construction of albumin multilayers via the electrostatic self-assembly (ESA) method was explored. Based on the results, it was possible to develop a fast, easy processing and shape-independent method for nonthrombogenic coating.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: JMTSAdoi: 10.1023/B:JMSC.0000008087.71937.71Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, Hangzhou 310027, China; email: jianji@mail.hz.zj.cnReferences: Bertrand, P., Jonas, A., Laschewsky, A., (2000) Macr. Rap. Comm., 21, p. 319;Ulman, A., (1996) Chem. Rev., 96, p. 1533; Sano, M., Lvov, Y., Kunitake, T., (1996) Annu. Rev. Mater. Sci., 26, p. 153; Houska, M., Brynda, E., (1997) J. Coll. Interf. Sci., 188, p. 243; Brynda, E., Houska, M., (1996) J. Coll. Interf. Sci., 183, p. 18; Keogh, R.J., Eaton, J.W., (1994) J. Lab. Clin. Med., 124, p. 537; Keogh, J.R., Velander, F.F., Eaton, W., (1992) J. Biomed. Mater. Res., 26, p. 441; Ji, J., Feng, L.X., Barbosa, M.A., (2001) Biomaterials, 22, p. 3015; Cheng, Z., Cheng, L., Dong, S., Yang, X., (2001) J. Electrochem. Soc., 148, pp. E227
Keywords: Adhesion; Adsorption; Albumin; Biocompatibility; Biological materials; Biopolymers; Blood; Charge transfer; Chemical bonds; Covalent binding; Desorption; Electron transfer; Electron transfer resistance; Electrostatic layer by layer adsorption; Electrostatics; Multilayers; polycation; Positive ions; Spectroscopic analysis; Static platelet adhesion

Human serum albumin adsorption on TiO 2 from single protein solutions and from plasma - Sousa, S.R.; Moradas-Ferreira, P.; Saramago, B.; Viseu Melo, L.; Barbosa, M.A. (LangmuirLangmuir, 2004)
In the present work, the adsorption of human serum albumin (HSA) on commercially pure titanium with a titanium oxide layer formed in a H 2O 2 solution (TiO 2 cp) and on TiO 2 sputtered on Si (TiO 2 sp) was analyzed. Adsorption isotherms, kinetic studies, and work of adhesion determinations were carried out. HSA exchangeability was also evaluated. Surface characterization was performed by atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), and wettability studies. The two TiO 2 surfaces have very distinct roughnesses, the TiO 2 sp having a mean R a value 14 times smaller than the one of TiO 2 cp. XPS analysis revealed consistent peaks representative of TiO 2 on sputtered samples as well as on Ti cp substrate after 48 h of H 2O 2 immersion. Nitrogen was observed as soon as protein was present, while sulfur, present in disulfide bonds in HSA, was observed for concentrations of protein higher than 0.30 mg/mL. The work of adhesion was determined from contact angle measurements. As expected from the surface free energy values, the work of adhesion of HSA solution is higher for the TiO 2 cp substrate, the more hydrophilic one, and lower for the TiO 2 sp substrate, the more hydrophobic one. The work of adhesion between plasma and the substrates assumed even higher values for the TiO 2 cp surface, indicating a greater interaction between the surface and the complex protein solutions. Adsorption studies by radiolabeling of albumin ( 125I-HSA) suggest that rapid HSA adsorption takes place on both surfaces, reaching a maximum value after ~60 min of incubation. For the higher HSA concentrations in solution, a multilayer coverage was observed on both substrates. After the adsorption step from single HSA solutions, the exchangeability of adsorbed HSA molecules by HSA in solution was evaluated. The HSA molecules adsorbed on TiO 2 sp seem to be more easily exchanged by HSA itself than those adsorbed on TiO 2 cp after 24 h. In contrast, after 72 h, nearly all the adsorbed albumin molecules effectively exchange with other albumin molecules.
Cited By (since 1996): 58Export Date: 21 November 2012Source: ScopusCODEN: LANGDdoi: 10.1021/la049158dPubMed ID: 15491210Language of Original Document: EnglishCorrespondence Address: Sousa, S.R.; Inst. de Engenharia Biomédica, Laboratório Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: ssousa@ibmc.up.ptChemicals/CAS: serum albumin, 9048-46-8; titanium dioxide, 1317-70-0, 1317-80-2, 13463-67-7, 51745-87-0; titanium, 7440-32-6; Serum Albumin; Solutions; titanium dioxide, 13463-67-7; Titanium, 7440-32-6References: Nakabayashi, N., Iwasaki, Y., (2000) European White Book on Fundamental Research in Materials Science, pp. pp70-71. , Rühle, M., Dosch, H., Mittemeijer, E. J.Van de Voorde, M. H., Eds.; Max Plank Institut fur Metallforschung: Stuttgart, Germany;Windler, M., Klabunde, R., (2001) Titanium in Medicine; Material Science, Surface Science, Engineering, Biological Responses and Medical Applications, pp. 703-746. , Brunette, D. M., Tengvall, P., Textor, M., Thomsen, P., Eds.; Springer-Verlag: Berlin, Germany; Larsson, C., Esposito, M., Liao, H., Thomsen, P., (2001) Titanium in Medicine: Material Science, Surface Science, Engineering, Biological Responses and Medical Applications, pp. 587-648. , Brunette, D.M., Tengvall, P., Textor, M., Thomsen, P., Eds.; Springer-Verlag: Berlin, Germany; Tengvall, P., Lundstrom, I., (1992) Clin. Mater., 9, pp. 116-134; Ostumi, E., Chapman, R.G., Liang, M.N., Meluleni, G., Pier, G., Ingberg, D.E., Whitesides, G.M., (2001) Langmuir, 17, pp. 6336-6343; Gehanno, V., Freitas, P.P., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Soares, J.C., Silva, M.F., (1999) IEEE Trans. Magn., 35, pp. 4361-4367; Owens, D.K., Wendt, E.C., (1969) J. Appl. Polym. Sci., 13, pp. 1741-1747; Kerkeb, M.L., González-Caballero, F., Chibowski, E., (1993) J. Colloid Interface Sci., 159, pp. 439-443; (1993) A Guide to Radioiodination Techniques; Amersham Life Science: Little Chalfont, p. 64. , Iodine-125, Buckinghamshire, U.K; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., (2001) J. Biomed. Mater. Res., 55, pp. 45-53; Williams, D.F., Askill, I.N., Smith, R., (1985) J. Biomed. Mater. Res., 19, pp. 313-320; Sheardown, H., Cornelius, R.M., Brash, J.L., (1997) Colloids Surf., B, 10, pp. 29-33; Du, Y.J., Cornelius, R.M., Brash, J.L., (2000) Colloids Surf., 17, pp. 59-67; Yu, X.J., Brash, J.L., (1993) Test Procedures for the Blood Compatibility of Biomaterials, pp. 287-330. , Dawids, S., Ed.; Kluwer Academic Publishers: Dordrecht, The Netherlands; Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., (1985) Anal. Biochem., 150, pp. 76-85; Shirkhanzadeh, M., (1996) J. Mater. Sci.: Mater. Med., 6, pp. 206-210; Kilpadi, D.V., Raikar, G.N., Liu, J., Lemons, J.E., Vohra, Y., Gregory, J.C., (1998) J. Biomed. Mater. Res., 40, pp. 646-659; Lausmaa, J., Kasemo, B., Mattsson, H., (1990) Appl. Surf. Sci., 44, pp. 133-146; Armstrong, N.R., Quinn, R.K., (1977) Surf. Sci., 67, pp. 451-468; Leitao, E., Barbosa, M.A., Degroot, K., (1997) J. Mater. Sci.: Mater. Med., 8, pp. 423-426; Ramqvist, L., Hamrin, K., Johansso, G., Fahlman, A., Nordling, C., (1969) J. Phys. Chem. Solids, 30, pp. 1835-1847; Hanawa, T., Ota, M., (1992) Appl. Surf. Sci., 55, pp. 269-276; Kuznetsov, M.V., Zhuravlev, J.F., Gubanov, V.A., (1992) J. Electron Spectrosc. Relat. Phenom., 58, pp. 169-176; Ikeo, N., Iijima, Y., Niimura, N., Sigematsu, M., Tazava, T., Matsumoto, S., Kojima, K., Nagasawa, Y., (1991) Handbook of X-ray Photo-electron Spectroscopy JEOL, , Tokyo, Japan; Porte-Durrieu, M.C., Labrugere, C., Villars, F., Lefebvre, F., Dutoya, S., Guette, A., Bordenave, L., Baquey, C., (1999) J. Biomed. Mater. Res., 46, pp. 368-375; Wagner, C.D., Riggs, W.M., Davis, L.E., Moulder, J.F., (1979) Handbook of X-ray Photoelectron Spectroscopy, , Mulenberg, G. E., Ed.; Perkin Elmer Corp: Eden Prairie, MN; Barr, T.L., (1991) J. Vac. Sci. Technol., A, 9, pp. 1793-1805; Wälivaara, B., Aronsson, B.O., Rodahl, M., Lausmaa, J., Tengvall, P., (1994) Biomaterials, 15, pp. 827-834; Oji, M.O., Wood, J.V., Downes, S., (1999) J. Mater. Sci.: Mater. Med., 10, pp. 869-872; Pan, J., Liao, H., Leygraf, C., Thierry, D., Li, J., (1998) J. Biomed. Mater. Res., 40, pp. 244-256; Ratner, B.D., Horbett, T.A., Shuttleworth, D., Thomas, H.R., (1981) J. Colloid Interface Sci., 83, pp. 630-642; Lindberg, B., Maripuu, R., Siegbahn, K., Larsson, R., Golander, C.G., Eriksson, J.C., (1983) J. Colloid Interface Sci., 95, pp. 308-321; Auditore, A., Satriano, C., Coscia, U., Ambrosone, G., Parisi, V., Marietta, G., (2002) Biomol. Eng., 19, pp. 85-90; Miller, B., Treppo, S., Voigt, A., Zingg, W., Neumann, A.W., (1993) Colloids Surf., 69, pp. 203-208; Serro, A.P.V., Fernandas, A.C., Saramago, B.D.V., (1997) Colloids Surf., A, 125, pp. 209-219; Lopes, M., Monteiro, F., Santos, J., Serro, A., Saramago, B., (1999) J. Biomed. Mater. Res., 45, pp. 370-375; Ferraz, M.P., Monteiro, F.J., Serro, A.P., Saramago, B., Gibson, I.R., Santos, J.D., (2001) Biomaterials, 22, pp. 3105-3112; Vogler, E.A., (1993) Surfactant Science Series, 49, pp. 183-250. , Wettability; Berg, J. C., Ed.; Marcel Dekker: New York; Feng, B., Weng, J., Yang, B.C., Qu, S.X., Zhang, X.D., (2003) Biomaterials, 24, pp. 4663-4670; Morra, M., Cassinelli, C., Cascardo, G., Cahalan, P., Cahalan, L., Fini, M., Giardino, R., (2003) Biomaterials, 24, pp. 4639-4654; Wälivaara, B., Lundstrom, I., Tengvall, P., (1993) Clin. Mater., 12, pp. 141-148; Lincks, J., Boyan, B.D., Blanchard, C.R., Lohmann, C.H., Liu, Y., Cochran, D.L., Dean, D.D., Schwartz, Z., (1998) Biomaterials, 19, pp. 2219-2232; Ong, J.L., Carnes, D.L., Cardenas, H.L., Cavin, R., (1997) Implant Dent., 6, pp. 19-24; Ricci, J.L., Spivak, J.M., Blumenthal, N.C., (1991) The Bone Biomaterial Interface, pp. 334-349. , Davis, J. E., Ed.; University of Toronto Press: Toronto; Busscher, H.J., Vanpelt, A.W.J., Deboer, P., Dejong, H.P., Arends, (1984) J. Colloids Surf., 9, pp. 319-331; Hitchcock, S.J., Carroll, N.T., Nicholas, M.G., (1981) J. Mater. Sci., 16, pp. 714-732; Rakhorst, G., Van Der Mei, H.C., Van Oeveren, W., Spijker, H.T., Int, B.H.J., (1999) J. Artif. Organs, 22, pp. 35-39; Martins, M.C., Ratner, B.D., Barbosa, M.A., (2003) J. Biomed. Mater. Res., 67 A, pp. 158-171; Sigal, G.B., Mrksich, M., Whitesides, G.M., (1998) J. Am. Chem. Soc., 120, pp. 3464-3473; Prime, K.L., Whitesides, G.M., (1991) Science, 252, pp. 1164-1167; Vandulm, P., Norde, W., (1983) J. Colloid Interface Sci., 91, pp. 248-255; Williams, R.L., Williams, D.F., (1988) J. Colloid Interface Sci., 126, pp. 596-603; Serro, A.P.V.A., Fernandes, A.C., Saramago, B.D.V., Norde, W., (1999) J. Biomed. Mater. Res., 46, pp. 376-381; Norde, W., Anusiem, A.C.I., (1992) Colloids Surf., 86, pp. 73-80; Young, B.R., Pitt, W.G., Cooper, S.L., (1988) J. Colloid Interface Sci., 125, pp. 246-260; Feng, L., Andrade, J.D., (1994) Biomaterials, 5, pp. 323-333; Norde, W., (1986) Adv. Colloid Interface Sci., 25, pp. 267-340; Kurrat, R., Prenosil, J.E., Ramsden, J.J., (1987) J. Colloid Interface Sci., 186, pp. 1-8; Brash, J.L., Uniyal, S., Samak, Q., (1974) Trans. Am. Soc. Artif. Intern. Organs, 20 A, pp. 69-76
Keywords: Adsorption; article; Atomic force microscopy; Blood; chemistry; human; Human serum albumin (HSA); Humans; hydrophobicity; Multilayers; plasma; Plasmas; Plastic surgery; Proteins; Radiolabeling; Serum Albumin; solution and solubility; Solutions; Substrates; Surface characterization; Surface Properties; surface property; Titanium; Titanium dioxide; X ray photoelectron spectroscopy

"In vitro" bioactivity evaluation of CaO-P 2O 5 glass-hydroxylapatite thin coatings produced by pulsed laser deposition - Arias, J.L.; Liste, S.; González, P.; Serra, J.; León, B.; Ferraz, M.P.; Monteiro, F.J.; Giao, D.; Pérez-Amor, M. (Transactions - 7th World Biomaterials CongressTrans. World Biomater. Congr., 2004)
The synthesis of coatings based on hydroxyapatites (HA) and glass modified hydroxyapatite targets by pulsed laser deposition, was presented. It was observed that coatings produced from HA targets keep their crystallinity through all their thickness, while there is a loss of crystallinity towards the surface of the HA+1.5G coatings. On immersion in SBF for three days, the coatings produced from HA targets suffered a loss of crystallinity near the surfaces, while the crystallinity of the coatings produced from HA+1.5G targets increased. It was also observed that addition of 1.5wt% of CaO-P 2O 5 glasses to HA thin coatings produced by pulsed laser deposition leads to a significant structural change of the coating surface.
Conference code: 64310Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Arias, J.L.; Depto. de Física Aplicada, Universidade de Vigo, Lagoas-Marcosende 9, E-36200 Vigo, SpainReferences: Arias, J.L., (1997) J Mater Sci Mater Med, 8, p. 873;Ferraz, M.P., (1999) J Biomed Mater Res, 45, p. 373; Ferraz, M.P., (1999) J. Mat Sci Mat Med, 10, p. 567
Keywords: Apatites; Bioactivity; Calcium Compounds; Coatings; Crystalline materials; Crystalline phases; hydroxyapatite; Mixtures; Phosphorus Compounds; Pressure effects; Pulsed laser deposition; Scanning electron microscopy; Substrates; Thin coatings; X ray diffraction; X ray photoelectron spectroscopy

In Vitro Cytocompatibility of Osteoblastic Cells Cultured on Chitosan-Organosiloxane Hybrid Membrane - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Fernandes, M.H. (Key Engineering MaterialsKey Eng Mat, 2004)
Chitosan-silicate hybrids were synthesized using γ-glycidoxypropyltrimethoxysilane (GPSM) as the agent to cross-link the chitosan chains. Fourier-transform infrared (PT-IR) spectroscopy was used to analyze the structures of the hybrids. The swelling ability and the cytocompatibility of the hybrids were investigated as a function of the GPSM concentration. The swelling of the hybrids was suppressed by addition of GPSM. MG63 human osteoblastic cells were cultured on the hybrids. The adhesion and proliferation of the MG63 cells cultured on the chitosan-GPSM hybrid surface were improved comparing to that on chitosan membrane, regardless the GPSM concentration.
Conference code: 62053Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Shirosaki, Y.; Biomaterial Laboratory, Faculty of Engineering, Okayama University, Tsushima, Okayama-shi 700-8530, JapanReferences: Chandy, T., Sharma, P.C., (1990) Biomat Art Cells Art Org, 18, pp. 1-24;Jameela, S.R., Jayakrishnan, A., (1995) Biomaterials, 16, pp. 769-775; Nishi, C., Nakajima, N., Ikada, Y., (1995) J Biomed Mater Res., 29, pp. 829-834; Ren, L., Tsuru, K., Hayajkawa, S., Osaka, A., (2002) Biomaterials, 23, pp. 4765-4773
Keywords: Biocompatibility; Biological membranes; biosynthesis; Cell culture; Cells; chitosan; Chitosan-inorganic hybrid; Crosslinking; Cytocompatibility; Fourier transform infrared spectroscopy; Nuclear magnetic resonance spectroscopy; Organic polymers; Osteoblastic cell (MG63); Structural analysis; Synthetic polymers; Tissue; Tissue engineering; γ-Glycidoxypropyltrimethoxysilane (GPSM)

In Vitro Mineralisation of Human Bone Marrow Cells Cultured on Bonelike® - Costa, M.A.; Gutierres, M.; Almeida, L.; Lopes, M.A.; Santos, J.D.; Fernandes, M.H. (Key Engineering MaterialsKey Eng Mat, 2004)
Bonelike® is a CaO-P 2O 5 based glass-reinforced hydroxyapatite (HA) designed to mimic the inorganic composition of the bone tissue. This work evaluates the response of human bone marrow cells to Bonelike® concerning cell proliferation and osteoblast differentiation. HA was used as control material. Results showed that Bonelike® allowed the proliferation of bone marrow cells and their complete differentiation, as evidenced by the formation of cell-mediated mineralisation. In comparison with HA, Bonelike® had a positive effect on the expression of alkaline phosphatase and also on the formation of a mineralised matrix, two osteoblast markers.
Conference code: 62053Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Costa, M.A.; Inst. Cie. Blomed. de Abel Salazar, Universidade do Porto, Largo Abel Salazar, 4000 Porto, PortugalReferences: Santos, J.D., Campbell, J.K., Winston, G.H., European Patent N° WO0068164, 2000Lopes, M.A., Knowles, J.C., Santos, J.D., (2000) Biomaterials, 21, p. 1905;Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res.:App. Biomater., 48, p. 734; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., (1998) J. Biomed. Mater. Res., 41, p. 649; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., (2000) Biomaterials, 21, p. 1165; Ferraz, M.P., Fernandes, M., Santos, J.D., Monteiro, F.J., (2001) J. Mat. Sci.: Mat. Med., 12, p. 629; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463; Duarte, F., Santos, J.D., Afonso, A., Advanced Materials Forum, , in press; Coelho, M.J., Fernandes, M.H., (2000) Biomaterials, 21, p. 1095; Kleerekoper, M., (1996) Principles of Bone Biology, p. 1053. , Academic Press
Keywords: Bone; Bonelike®; Cell culture; cell proliferation; Composition; Grafts; Human bone marrow cells; hydroxyapatite; In vitro mineralisation; mineralization; Scanning electron microscopy; Sintering; X ray diffraction

In Vivo Behaviour of Bonelike®/PLGA Hybrid: Histological Analysis and Peripheral Quantitative Computed Tomography (pQ-CT) Evaluation - Oliveira, J.M.; Kawai, T.; Lopes, M.A.; Ohtsuki, C.; Santos, J.D.; Afonso, A. (Key Engineering MaterialsKey Eng Mat, 2004)
The present work consisted in assessing the in vivo biological behaviour of novel Bonelike®/PLGA hybrid materials through subcutaneous and tibiae implantations for a 4 week period using an animal model. No sign of inflammation was observed as a result of subcutaneous implantation, which reveals that these materials were well-tolerated by the soft tissues. pQ-CT analysis demonstrated that the implanted materials were highly osteointegrated in bone tissue. SEM analysis at bone defect area revealed that Bonelike® resorption occurred after 4 weeks of implantation. Although the osteoconductive properties of Bonelike® have been reported in literature, the present work allowed to demonstrate that the silane-coupling agent and the PLGA treatments do not significantly modify the biological performance of Bonelike®. This result is strongly encouraging since Bonelike®/PLGA hybrid materials are being developed for bone tissue healing/regeneration purposes with simultaneous delivery of therapeuthic molecules.
Conference code: 62053Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Oliveira, J.M.; Inst. de Engenharia Biomédica, Lab. de Biomaterials, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jmoliv@fe.up.ptReferences: Solheim, E., Pinholt, E., Bang, G., (1992) Journal Neurosurgery, 76, pp. 275-279;Laurecin, C.T., Attawia, M.A., Lu, L.Q., Borden, M.D., Lu, H.H., Gorum, W.J., Lieberman, J.R., (2001) Biomaterials, 22, pp. 1271-1277; Nielsen, F.F., Karring, T., Gogolewski, S., (1992) Acta Orthop Scandinavica, 63, pp. 66-69; Jiang, G., Woo, B.H., Kang, F., Singh, J., Deluca, P.P., (2002) Journal of Controlled Release, 79, pp. 137-145; Duarte, F., Lopes, M.A., Santos, J.D., European Cells and Materials, , in press; Duarte, F., Afonso, A., Santos, J.D., Advanced Materials Forum, , in press; Oliveira, J.M., Lopes, M.A., Kawai, T., Ohtsuki, C., Santos, J.D., Afonso, A., Advanced Materials Forum, , in press; Santos, J.D., Campbell, J.K., Winton, G.H., European Patent N° W00068164 (2000)Oliveira, J.M., Miyazaki, T., Lopes, M.A., Ohtsuki, C., Santos, J.D., Biomaterials, , submitted
Keywords: Biodegradation; Bonelike®; Computerized tomography; Histological analysis; histology; hydroxyapatite; In vivo studies; Organic polymers; PLGA; pQ-CT; Silanes; Sintering; Synthetic polymers; Tibiae implantations; Tissue

Influence of characteristics of the starting hydroxyapatite powders and of deagglomeration procedure, on rheological behaviour of HA suspensions - Lemos, A.F.; Santos, J.D.; Ferreira, J.M.F. (Materials Science ForumMater Sci Forum, 2004)
In order to evaluate how the characteristics of starting HA powders affect their dispersion ability, several tests were made, including particle size distribution, particle morphology (SEM) and rheological measurements of the suspensions. To enable the preparation of concentrated suspensions as high as possible, the influence of deagglomeration procedure on rheological behaviour of hydroxyapatite aqueous suspensions was evaluated. The results revealed significant differences in the dispersing ability of the powders and on the maximum achievable solids loading. In fact, the maximum solids volume fraction that was possible to incorporate in the initial suspension of HA R was only 35-vol.%, while with the HA S it has been possible to start from 45-vol.% suspensions. Ball milling revealed to be more efficient than planetary milling in the preparation of HA R suspensions, and enabled to achieve a maximum solids volume fraction of 45-vol.% at the end of long milling period, which included successive incremental additions of powder. The powder HA S exhibited a much better dispersing ability, enabling the preparation of 60-vol.% solids only after two hours of planetary milling.
Conference code: 63332Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: MSFOELanguage of Original Document: EnglishCorrespondence Address: Ferreira, J.M.F.; Dept. of Ceramics Engineering, CICECO, Univ. of Aveiro, 3810-193 Aveiro, Portugal; email: jmf@cv.ua.ptReferences: Kanazawa, T., (1989) Inorganic Phosphate Materials, 52, p. 15. , Materials Science Monographs, (Elsevier Science Publishers, Amsterdam);Elliot, J.C., (1994) Structure and Chemistry of the Apatites and Other Calcium Orthophosphates. Studies in Organic Chemistry, 18. , Elsevier Science, Netherlands; Ohgushi, H., Okumura, M., Yoshikawa, T., Inoue, K., Senpuku, N., Tamai, S., Shors, E.C., (1992) J. Biomed. Mater. Res., 26, p. 885; Saggio-Woyanski, J., Scott, C., (1992) Am. Ceram. Soc. Bull., 71, p. 1674; Lyckfeldt, O., Ferreira, J.M.F., (1998) J. Eur. Ceram. Soc., 18, p. 131; Lorenzo, L.M.R., (1999), PhD Thesis MadridOlhero, S.M., Ferreira, J.M.F., (2003) Powder Thecnology, , accepted for publication
Keywords: Agglomeration; Bioceramics; crystallography; Deagglomeration; Foaming processes; hydroxyapatite; medicine; morphology; Particle size analysis; Powder characteristics; Powders; rheology; Scanning electron microscopy; Sedimentation; Sintering

Laser surface modification of hydroxyapatite and glass-reinforced hydroxyapatite - Queiroz, A.C.; Santos, J.D.; Vilar, R.; Eugénio, S.; Monteiro, F.J. (BiomaterialsBiomaterials, 2004)
Surface treatment of materials with excimer laser radiation often results in the formation of a rough columnar or cone-shaped surface topography, which leads to a considerable increase in the surface area. As a result, the search for a non-porous bioactive material with adequate mechanical properties and a high surface to volume ratio, similar to porous materials, which could be used for drug delivery in the treatment of periodontitis, justified assessing excimer laser surface treatment to promote controlled roughning of hydroxyapatite (HA) and glass-reinforced hydroxyapatite (GR-HA). A KrF excimer laser with 248nm radiation wavelength and 30ns pulse duration was used for surface modification. The laser treatment was carried out in air, using wide ranges of radiation fluence and number of laser pulses. In order to identify the physico-chemical changes induced by the laser treatment and the column formation mechanisms in these materials, the treated surfaces were characterised by laser profilometry, scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and Fourier transform infra-red spectroscopy (FTIR). Laser processing induced the formation of a surface topography consisting of cone-shaped features. The constitution of the surface layer was also modified, as revealed by FTIR, XPS and XRD. This work has shown that laser surface modification increases the surface area of HA and GR-HA and is a promising technique to increase the reactivity and drug delivery capability of both materials. © 2003 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2003.11.054PubMed ID: 15120506Language of Original Document: EnglishCorrespondence Address: Queiroz, A.C.; INEB-Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180, Porto, Portugal; email: aqueiroz@ineb.up.ptChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; Biocompatible Materials; Durapatite, 1306-06-5; Macromolecular SubstancesReferences: Krejci, C.B., Bissada, N.F., Farah, C., Greenwell, H., Clinical evaluation of porous and nonporous hydroxyapatite in the treatment of human periodontal bony defects (1987) J Periodontol, 58, pp. 521-528;Seymour, R.A., Heasman, P.A., MacGregor, I.D.M., The pathogenesis of periodontal disease (1992) Drugs, Diseases, and the Periodontium, pp. 1-10. , I.D.M. MacGregor. Oxford: Oxford University Press; Systemic antibiotics in periodontics (1996) J Periodontol, 67, pp. 831-838; Steinberg, D., Friedman, M., Soskolne, A., Sela, M.N., A new degradable controlled release device for treatment of periodontal disease: In vitro release study (1990) J Periodontol, 61, pp. 393-398; Soskolne, W.A., Heasman, H.A., Stabholz, A., Smart, G.J., Palmer, M., Flashner, M., Newman, H.N., Sustained local delivery of chlorhexidine in the treatment of periodontitis: A multi-center study (1997) J Periodontol, 68, pp. 32-38; Prado Da Silva, M.H., Lemos, A.F., Gibson, I.R., Ferreira, J.M.F., Santos, J.D., Porous glass reinforced hydroxyapatite materials produced with different organic additives (2002) J Non-Cryst Solids, 304, pp. 286-292; Barinov, S.M., Baschenko, Y.V., Application of ceramic composits as implants: Result and problem (1992) Bioceramics and the Human Body, pp. 206-210. , A. Krajewski. UK: Elsevier Science Publishers; Koshino, T., Murase, T., Takagi, T., Saito, T., New bone formation around porous hydroxyapatite wedge implanted in opening wedge high tibial osteotomy in patients with osteoarthritis (2001) Biomaterials, 22, pp. 1579-1582; Nishihara, K., Studies on peri-root tissue formation around new type artificial root made of dense hydroxyapatite (1993) Clin Mater, 12, pp. 159-167; Chang, B., Lee, C., Hong, K., Youn, H., Ryu, H., Chung, S., Park, K., Osteoconduction at porous hydroxyapatite with various pore configurations (2000) Biomaterials, 21, pp. 1291-1298; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tensions, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Santos, J.D., Silva, P.L., Knowles, J.C., Talal, S., Monteiro, F.J., Reinforcement of hydroxyapatite by adding P 2O 5-CaO glasses with Na 2O, K 2O and MgO (1996) J Mater Sci: Mater Med, 7, pp. 187-189; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of effects of glass on response of osteosarcoma cells to plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings (1999) J Biomed Mater Res, 47, pp. 603-611; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P2O5 Glass hydroxyapatite double-layer plasma-sprayed coating: In vitro bioactivity evaluation (1999) J Biomed Mater Res, 45, pp. 376-383; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Gibson, I.R., Knowles, J.C., Adsorption and release of sodium ampicillin from hydroxyapatite and glass-reinforced hydroxyapatite composites (2001) Biomaterials, 22, pp. 1393-1400; Clèries, L., Fernández-Pradas, J.M., Morenza, J.L., Behaviour in simulated body fluid of calcium phosphate coating obtained by laser ablation (2000) Biomaterials, 21, pp. 1861-1865; D'Alession, L., Teghil, R., Zaccardo, I., Ferro, D., Marotta, V., Pulsed laser ablation and deposition of bioactive glass as coating material for biomedical applications (1999) Appl Surf Sci, 138-139, pp. 527-532; Fernández-Pradas, J.M., Clèries, L., Serra, P., Sardin, G., Morenza, J.L., Evolution of the depositon rate during pulsed laser deposition of hydroxyapatite coatings and its relation with target morphology (2001) Appl Phys a, 72, pp. 613-618; Zeng, H., Lacefield, W.R., XPS, EDX and FTIR analysis of pulsed laser deposited calcium phosphate bioceramic coatings: The effects of various process parameters (2000) Biomaterials, 21, pp. 23-30; Serra, P., Fernández-Pradas, J.M., Sardin, G., Morenza, J.L., Interaction effects of an excimer laser beam with hydroxyapatite targets (1997) Appl Surf Sci, 109-110, pp. 384-388; Serra, P., Morenza, J.L., Fluence dependence of hydroxyapatite laser ablantion plumes (1998) Thin Solid Films, 335, pp. 43-48; Foltyn, S.R., Dye, R.C., Ott, K.C., Peterson, E., Hubbard, K.M., Hutchinson, W., Muenchausen, R.E., Wu, X.D., Target modification in the excimer laser deposition of YBa 2Cu 3O 7-x thin films (1991) Appl Phys Lett, 59, pp. 594-596; Oliveira, V., Conde, O., Vilar, R., UV laser micromachining of ceramic materials: Formation of columnar topographies (2001) Adv Eng Mater, 3, pp. 75-81; Ricci, J.L., Alexander, H., Laser microtexturing of implant surfaces for enhanced tissue integration (2001) Key Eng Mater, 198-199, pp. 179-202; Khor, K.A., Vreeling, A., Dong, Z.L., Cheang, P., Laser treatment of plasma sprayed HA coatings (1999) Mater Sci Eng a, 266, pp. 1-7; Sobol, E.M., (1995) Phase transformations and ablation in laser-treated solids, , New York: Wiley; Underwood, E.E., (1970) Quantitative Stereology, , Reading: Addison-Wesley;; Underwood, E.E., Banerji, K., Quantitative fractography (1987) ASM-Metals Handbook, 12; Rey, C., Shimizu, M., Collins, B., Glimcher, M.J., Resolution enhanced Fourier transform infrared spectroscopy study of the environment of phosphate ion in the early deposits of a solid phase calcium phosphate in bone and enamel and their evolution with age: Investigations in the ν 4 PO 4 3- domain (1990) Calcif Tissue Int, 46, pp. 384-394; Rey, C., Shimizu, M., Collins, B., Glimcher, M.J., Resolution enhanced Fourier transform infrared spectroscopy study of the environment of phosphate ion in the early deposits of a solid phase calcium phosphate in bone and enamel and their evolution with age: Investigations in the ν 3 PO 4 3- domain (1991) Calcif Tissue Int, 49, pp. 383-388; Elliott, J.C., Structure and chemistry of apatites and other calcium orthophosphates (1994) Inorganic Chemistry, 18, p. 50. , Elliott J.C. Amsterdam: Elsevier Science; Dupraz, A., Nguyen, T.P., Richard, M., Dalcusi, G., Passuti, N., Influence of a cellulosic ether carrier on the structure of biphasic calcium phosphate ceramic particles in an injectable composite material (1999) Biomaterials, 20, pp. 663-673; Franke, R., Chassé, Th., Streubel, P., Meisel, A., Auger parameters and relaxation energies of phosphorus in solid compounds (1991) J Electron Spectrosc Relat Phemon, 56, pp. 381-388; Heitz, J., Pedarning, J.D., Bauerle, D., Petzow, G., Excimer laser ablation and micro-patterning of ceramic Si 3N 4 (1997) Appl Phys a, 65, pp. 259-261; Foltyn, S.R., Surface modification of materials by cumulative laser irradiation (1994) Pulsed Laser Deposition of Thin Films, pp. 89-113. , D.B. Chrisey, & G.K. Hubler. New York: Wiley; Lappalainen, J., Frantti, J., Lanto, V., Surface structure and particulate generation in Pb 0.97Nd 0.02(Zr 0.55Ti 0.45)O 3 ablation targets during pulsed laser deposition (1999) J Am Cer Soc, 82, pp. 889-896; Óbrien, T.P., Lawler, J.F., Lunney, J.G., Blau, W.J., The effect of laser fluence on the ablation and deposition of YBa 2Cu 3O 7 (1992) Mater Sci Eng, 13, pp. 9-13; Man, H.C., Zhang, X.M., Yue, T.M., Lau, W.S., Excimer-laser surface modification of engineering ceramics for adhesive bonding (1997) J Mater Proc Techn, 66, pp. 123-129; Sánchez, F., Morenza, J.L., Trtik, V., Characterization of the progressive growth of columns by excimer laser irradiation of silicon (1999) Appl Phys Lett, 75, pp. 3303-3305; Pedraza, A., Fowlkes, J.D., Lowndes, D.H., Self organized silicon microcolumns arrays generated by pulsed laser irradiation (1999) Appl Phys a, 69, pp. 731-S734; Usoskin, A., Freyhardt, H.C., Krebs, H.U., Influence of light scattering on the development of laser induced ridge-cone structure on target surfaces (1999) Appl Phys a, 69, pp. 823-S826
Keywords: article; Biocompatible Materials; Biomaterials; drug delivery system; Durapatite; Excimer laser; Excimer lasers; Fourier transform infrared spectroscopy; FTIR; glass; hydroxyapatite; infrared spectroscopy; laser; Lasers; Macromolecular Substances; materials testing; Molecular Conformation; Non-porous bioactive materials; periodontitis; physical chemistry; porosity; priority journal; Profilometry; Radiation Dosage; Reinforcement; Scanning electron microscopy; Surface area; Surface modification; Surface Properties; Surface treatment; topography; X ray diffraction; X ray diffraction analysis; X ray photoelectron spectroscopy; XPS; XRD

A model for educational simulation of infant cardiovascular physiology - Goodwin, J.A.; van Meurs, W.L.; Sá Couto, C.D.; Beneken, J.E.W.; Graves, S.A. (Anesthesia and AnalgesiaAnesth. Analg., 2004)
Full-body patient simulators provide the technology and the environment necessary for excellent clinical education while eliminating risk to the patient. The extension of simulator-based training into management of basic and critical situations in complex patient populations is natural. We describe the derivation of an infant cardiovascular model through the redefinition of a complete set of parameters for an existing adult model. Specifically, we document a stepwise parameter estimation process, explicit simplifying assumptions, and sources for these parameters. The simulated vital signs are within the target hemodynamic variables, and the simulated systemic arterial pressure wave form and left ventricular pressure volume loop are realistic. The system reacts appropriately to blood loss, and incorporation of aortic stenosis is straightforward. This infant cardiovascular model can form the basis for screen-based educational simulations. The model is also an essential step in attaining a full-body, model-driven infant simulator.
Cited By (since 1996): 19Export Date: 21 November 2012Source: ScopusCODEN: AACRAdoi: 10.1213/01.ANE.0000134797.52793.AFPubMed ID: 15562049Language of Original Document: EnglishCorrespondence Address: Goodwin, J.A.; Nemours Children's C., 807 Children's Way, Jacksonville, FL 32207, United States; email: jgoodwin@nemours.orgReferences: Good, M.L., Gravenstein, J.S., Training for safety in an anesthesia simulator (1993) Semin Anesth, 12, pp. 235-250;Gaba, D.M., DeAnda, A., The response of anesthesia trainees to simulated critical incidents (1989) Anesth Analg, 68, pp. 444-451; Howard, S.K., Gaba, D.M., Fish, K.J., Anesthesia crisis resource management training: Teaching anesthesiologists to handle critical incidents (1992) Aviat Space Environ Med, 63, pp. 763-770; Euliano, T.Y., Caton, D., Van Meurs, W., Good, M.L., Modeling obstetric cardiovascular physiology on a full-scale patient simulator (1997) J Clin Monit, 13, pp. 293-297; Halamek, L.P., Kaegi, D.M., Gaba, D.M., Time for a new paradigm in pediatric medical education: Teaching neonatal resuscitation in a simulated delivery room environment (2000) Pediatrics, 106, pp. E45; Beneken, J.E.W., (1965) A Mathematical Approach to Cardiovascular Function: The Uncontrolled Human System, , [PhD thesis]. Medisch Fysisch Institut TNO, Utrecht, The Netherlands; Beneken, J.E.W., DeWit, B., A physical approach to hemodynamic aspects of the human cardiovascular system (1967) Physical Bases of Circulatory Transport: Regulation and Exchange, pp. 1-45. , Reeve EB, Guyton AC, eds. Philadelphia: Saunders; Wesseling, K.H., Settels, J.J., Baromodulation explains short-term blood pressure variability (1985) Psychophysiology of Cardiovascular Control, pp. 69-97. , Orlebeke JF, Mulder G, van Doornen LJP, eds. New York: Plenum Press; Van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit, 13, pp. 317-324; Pruitt, A.W., Gersony, W.M., The cardiovascular system (1992) Nelson Textbook of Pediatrics. 14th Ed., pp. 1125-1227. , Behrman RE, ed. Philadelphia: Saunders; Gregory, G.A., Monitoring during surgery (1994) Pediatric Anesthesia, pp. 261-279. , Gregory GA, ed. New York: Churchill Livingstone; Graham Jr., T.P., Jarmakani, M.M., Evaluation of ventricular function in infants and children (1971) Pediatr Clin North Am, 18, pp. 1109-1132; Wodey, E., Plady, P., Copin, C., Comparative hemodynamic depression of sevoflurane versus halothane in infants (1997) Anesthesiology, 87, pp. 795-800; Suga, H., Sagawa, K., Shoukas, A.A., Load independence of the instantaneous pressure-volume ratio of the canine left ventricle and effects of epinephrine and heart rate on the ratio (1973) Circ Res, 2, pp. 314-322; Ten Voorde, B., (1992) Modeling the Baroreflex: A System Analysis Approach, , [PhD thesis]. Vakgroep Medische Fysica, Amsterdam, The Netherlands; Cunningham, M.D., Bedside pulmonary function testing of infants (1990) Essentials of Pediatric Intensive Care, pp. 878-883. , Levin DL, Morriss FC, eds. St. Louis: Quality Medical; Strafford, M.A., Cardiovascular physiology (1996) Smith's Anesthesia for Infants and Children, pp. 69-104. , Motoyama EK, Davis PJ, eds. St. Louis: Mosby; Lake, C.L., Cardiovascular anatomy and physiology (1992) Clinical Anesthesia, pp. 989-1020. , Barash PG, Cullen BF, Stoelting RK, eds. Philadelphia: Lippincott; Hsieh, K., Chen, P., Fu, S., A simple, noninvasive method to investigate vascular characteristics in children (1996) Angiology, 47, pp. 361-367; Stoelting, R.K., Miller, R.D., (2000) Basics of Anesthesia, pp. 364-375. , Philadelphia: Churchill Livingstone; Thilenius, O.G., Argilla, R.A., Angiographic right and left ventricular volume determination in normal infants and children (1974) Pediatr Res, 8, pp. 67-74; Drouin, E., Gournay, V., Calamel, J., Assessment of spontaneous baroreflex sensitivity in neonates (1997) Arch Dis Child Fetal Neonatal Ed, 76, pp. F108-12
Keywords: aging; Algorithms; Anesthesiology; aorta stenosis; Aortic Valve Stenosis; arterial pressure; article; Baroreflex; biological model; bleeding; Blood Loss, Surgical; cardiovascular function; Cardiovascular physiology; Computer simulation; education; heart ventricle pressure; hemodynamic parameters; Hemodynamic Processes; Humans; Infant; Models, Biological; priority journal; Pulmonary Circulation; simulation; Ventricular Function, Left; Ventricular Function, Right

New Method for the Incorporation of Soluble Bioactive Glasses to Reinforce Porous HA Structures - Lemos, A.F.; Santos, J.D.; Ferreira, J.M.F. (Key Engineering MaterialsKey Eng Mat, 2004)
The most widely used calcium-phosphate ceramic in clinical applications is hydroxyapatite, Ca 10(PO 4) 6(OH) 2, however its dissolution rate in the human body after implantation is too low to achieve good results and it has poor mechanical properties. Recently, glass reinforced hydroxyapatite composites (GR-HA) have been developed, in order to improve the mechanical properties and to increase the similarity between implants and bone. The addition of a P 2O 5 based glass to a hydroxyapatite matrix, promotes the liquid phase sintering, improving the mechanical properties of the final bodies, and enabling the formation of two other calcium-phosphate phases, which have a higher dissolution rate, more compatible with bone regeneration. However, some of these glass compositions are soluble in water, making their incorporation in aqueous slurry impossible. Therefore, the aim of the present work is to study a new alternative method for the incorporation of soluble P 2O 5 based glass into macroporous structures obtained by different methods.
Conference code: 62053Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Lemos, A.F.; Dept. of Ceramic Engineering, University of Aveiro, Campus de Santiago, 3810-193 Aveiro, Portugal; email: ilemos@cv.ua.ptReferences: De Groot, K., (1983) Bioceramics of Calcium Phosphates, , CRC Press, Boca Raton, FL;Wilson, L.L., Hench, J., (1993) An Introduction to Bioceramics, , World Scientific, UK; Hench, L.L., (1998) J. Am. Ceram. Soc., 81, p. 1075; Kohri, M., Miki, K., Waite, D.E., Nakajima, H., Okabe, T., (1993) Biomaterials, 14, p. 299; Krivak, N., Tas, A.C., (1998) J. Am. Ceram. Soc., 81, p. 2245; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., (1998) J. Biomed. Mater. Res., 41, p. 649; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., (2003) Advanced Materials Forum
Keywords: Bioactivation; Bioactive glass; Biocompatibility; Bone; Dissolution; glass; hydroxyapatite; Liquid phase sintering; Macroporous structures; Microstructure; Porous materials; Reinforced hydroxyapatite; Sintering; Slurries

Porous Hydroxyapatite and Glass Reinforced Hydroxyapatite for Controlled Release of Sodium Ampicillin - Queiroz, A.C.; Teixeira, S.; Santos, J.D.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2004)
Porous hydroxyapatite (HA) and glass reinforced hydroxyapatite (GRHA) with adequate macro and microporous structure were developed, aiming at being used as drug delivery carrier of antibiotics, for the in situ treatment of periodontitis. Materials were characterised by XRD and FTIR, presenting no changes from similar dense materials. Mercury intrusion porosimetry revealed micropores of less than 1 μm, accounting for 15% of the total porosity. Compression tests have shown close values for HA and GRHA, with the former showing slightly higher values of strength. Ampicillin adsorption was more effective on porous than on dense HA, and was similar for HA and GRHA.
Conference code: 62053Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Queiroz, A.C.; Inst. de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: aqueiroz@ineb.up.ptReferences: Krejci, C.B., Bissada, N.F., Farah, C., Greenwell, H., (1987) J Periodontol, 58, pp. 521-528;Seymour, R.A., Heasman, P.A., MacGregor, I.D.M., The pathogenesis of periodontal disease (1992) Drugs, Diseases, and the Periodontium, pp. 1-10. , MacGregor IDM, editor. Oxford: Oxford University Press; Steinberg, D., Friedman, M., Soskolne, A., Sela, M.N., (1990) J Periodontol, 61, pp. 393-398; Santos, J.D., Silva, P.L., Knowles, J.C., Talal, S., Monteiro, F.J., (1996) J Mater Sci: Mater Med, 7, pp. 187-189; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J Biomed Mat Res, 45, pp. 376-383; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., Key Engineering Materials, , submitted; Nishihara, K., (1993) Clin Materials, 12, pp. 159-167; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Gibson, I.R., Knowles, J.C., (2001) Biomaterials, 22, pp. 1393-1400
Keywords: Adsorption; Antibiotics; Coatings; Dense materials; Diseases; Drug delivery; Drug dosage; Fourier transform infrared spectroscopy; glass; Glass reinforced hydroxyapatite; hydroxyapatite; Mercury (metal); Porous; Porous materials; Scanning electron microscopy; Sodium; Strength of materials; Ultraviolet spectroscopy; X ray diffraction analysis

Production of porous hydroxyapatite with potential for controlled drug delivery - Queiroz, A.C.; Teixeira, S.; Santos, J.D.; Monteiro, F.J. (Materials Science ForumMater Sci Forum, 2004)
Porous hydroxyapatite was prepared in order to be used as a drug carrier and promote bone ingrowth. For this purpose, the microstructure should have interconnective pores and micro as well as macro porosity, for bone cell adhesion and bone ingrowth. The porous hydroxyapatite prepared by the burn-out method exhibits all these features. For measuring porosity, SEM analysis, mercury intrusion porosimetry and BET were used. FT-IR and XRD analysis revealed that only hydroxyapatite phase was present, being this result similar to the one found for dense samples. The morphology obtained appears to be well adapted to bone growth and drug adsorption.
Conference code: 63332Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: MSFOELanguage of Original Document: EnglishCorrespondence Address: Queiroz, A.C.; INEB, Inst. de Engenharia Biomédica, R do Campo Alegre, 823, 4150-180 Porto, Portugal; email: aqueiroz@ineb.up.ptReferences: Krejci, C.B., Bissada, N.F., Farah, C., Greenwell, H., (1987) J. Periodontology, 58, p. 521;Seymour, R.A., Heasman, P.A., MacGregor, I.D.M., The pathogenesis of periodontal disease (1992) Drugs, Diseases, and the Periodontium, , Oxford University Press; (1996) Journal of Periodontology, 67, p. 831; Soskolne, W.A., Heasman, H.A., Stabholz, A., Smart, G.J., Palmer, M., Flashner, M., Newman, H.N., (1997) Journal of Periodontology, 68, p. 32; Da Silva, M.H.P., Lemos, A.F., Gibson, I.R., Ferreira, J.M.F., Santos, J.D., (2002) J. of Non-crystaline Solids, 304, p. 286; Chang, B., Lee, C., Hong, K., Youn, H., Ryu, H., Chung, S., Park, K., (2000) Biomat., 21, p. 1291; Ewers, R., Simons, B., (1992) Biomaterials - Hard Tissue Repair and Replacement, , Elsevier Sc; Ohgushi, H., Okumura, M., Yoshikawa, T., Inoue, K., Senpuku, N., Tamai, S., Shors, E.C., (1992) Journal of Biomedical Materials Research, 26, p. 885; Barinov, S.M., Baschenko, Y.V., (1992) Bioceramics and the Human Body, , Elsevier Sc; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., (1997) J. Mater. Sc.: Materials in Medicine, 8, p. 731; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., (2003) Bioceramics, , accepted for; Santos, J.D., Monteiro, F.J., Gibson, I.R., Knowles, J.C., (2001) Biomaterial, 22, p. 1393
Keywords: Adsorption; Antibiotics; Bioceramics; Controlled drug delivery; Drug Carriers; Drug delivery; Fourier transform infrared spectroscopy; hydroxyapatite; morphology; Polyurethanes; porosity; Porous; Porous materials; Scanning electron microscopy; X ray diffraction analysis

Protein adsorption effect on in vitro acellular biodegradation of CaO-P 2O 5 glass ceramics - Dias, A.G.; Lopes, M.A.; Santos, J.D. (Materials Science ForumMater Sci Forum, 2004)
This work reports the in vitro accelular behaviour of a glass ceramic (45P 2O 5-45CaO-5MgO-5K 2O), which has significant potential for being used as an alloplastic bone graft. Experiments were carried out by immersing granule samples for a period up to 90 days in Trisbuffer solution at pH 7.4, in the presence and absence of a foetal bovine serum (FBS). The release of calcium, phosphorus, and potassium ions as well as the amount of protein adsorbed was followed by several techniques. The results obtained seem to indicate that the adsorption of proteins on the surface of the material, although causing an initial delay in the degradation, does not hamper the ionic exchange and therefore it is not a barrier for the degradation of the glass ceramic.
Conference code: 63332Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: MSFOELanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; Inst. de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Zeng, Chittur, K.K., Lacefield, W.R., (1999) Biomaterials, 20, p. 377;Ohta, Monna, H., Takahashi, S., (2001) J. Biomed. Mater. Res., 55, p. 409; Zyman, Z., Dedukh, N.V., Glusko, V.I., Shcherbyna, S.V., (2002) 17 th European Society for Biomaterials Conference Proceedings, , Barcelona; Krajewski, Malavoti, R., Piancatelli, A., (1996) Biomaterials, 17, p. 53; El-Ghannam, Ducheyne, P., Shapiro, I.M., (1997) Biomaterials, 18 (4); Takami, (1998) J. Biomed. Mater. Res., 40, p. 24; Puleo, A., Bizios, R., (1992) J. Biomed. Mater. Res., 26, p. 291; Dubois, C., Souchier, C., Couble, M.L., Exbrayat, P., Lissac, M., (1999) Biomat., 20, p. 1841; Green, J., Davies, M.C., Roberts, C.J., Tendler, S.J.B., (1997) Biomaterials, 18, p. 405; Haynes, C.A., Norde, W., (1994) Colloids and Surfaces B: Biointerfaces, 2, p. 517; Dias, G., Lopes, M.A., Gibson, I.R., Santos, J.D., (2002) 17 th Europ. Soc. for Biomat. Conf. Proc., , Barcelona; Chun, Na, S.W., Lee, J.H., Chung, J.P., Ryu, I.C., Kim, S.Y., (2002) Key Eng. Mat., 218-220, p. 149
Keywords: Adsorption; Bioceramics; Biodegradation; Calcium Compounds; Foetal bovine serum (FBS); Glass ceramics; Hard tissue; Ion exchange; Ionic strength; pH effects; Protein adhesion; Proteins; Tissue

Protein electrostatic self-assembly on poly(DL-lactide) scaffold to promote osteoblast growth - Zhu, H.; Ji, J.; Barbosa, M.A.; Shen, J. (Journal of Biomedical Materials Research - Part B Applied BiomaterialsJ. Biomed. Mater. Res. Part B Appl. Biomater., 2004)
The development of protein coating on 3D biodegradable scaffold based on electrostatic self-assembly (ESA) to promote osteoblast growth is reported. Poly (ethylenimine) (PEI) was employed to obtain a stable positively charged surface on poly(DL-lactide) (PDL-LA) substrate. An extracellular-matrix (ECM)-like biomacromolecule, gelatin, was chosen as the polyelectrolyte to deposit on the activated PDL-LA substrate via ESA technique. Osteoblast (MC3T3) was then cultured on unmodified and gelatin-modified PDL-LA scaffolds. Osteoblast testing regarding total intracellular protein content, total DNA content, cell activity, and cell morphology on the ECM-like multilayer-modified PDL-LA scaffold showed that osteoblast growth was promoted. It will be easy to replace the gelatin with osteoinductive proteins or other polyelectrolytes to promote specific osteoblast functions. In comparison with conventional coating methods, polyelectrolyte multilayers are easy and stable to prepare. They may be a good choice for the surface modification of complex biomedical devices, especially for the 3D tissue-engineering scaffold. These very flexible systems allow broad medical applications for drug delivery and tissue engineering. © 2004 Wiley Periodicals, Inc.
Cited By (since 1996): 14Export Date: 21 November 2012Source: ScopusCODEN: JBMRGdoi: 10.1002/jbm.b.30080PubMed ID: 15368240Language of Original Document: EnglishCorrespondence Address: Ji, J.; Dept. of Poly. Sci. and Engineering, Zhejiang University, Hangzhou 310027, China; email: jianji@mail.hz.zj.cnChemicals/CAS: DNA, 9007-49-2; gelatin, 9000-70-8; polyethyleneimine, 74913-72-7; polylactide, 26680-10-4; DNA, 9007-49-2; Gelatin, 9000-70-8; poly(lactide), 26969-66-4; PolyestersReferences: Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681;Kim, B.S., Mooney, D.J., Development of biocompatible synthetic extracellular matrices for tissue engineering (1998) Trend Biotechnol, 16, pp. 224-230; Hunter, A., Archer, C.W., Walker, P.S., Blunn, G.W., Attachment and proliferation of osteoblasts and fibroblasts on biomaterials for orthopaedic use (1995) Biomaterials, 16, pp. 287-295; Goldstein, A.S., Juarez, T.M., Helmke, C.D., Gustin, M.C., Mikos, A.G., Effect of convection on osteoblastic cell growth and function in biodegradable polymer foam scaffolds (2001) Biomaterials, 22, pp. 1279-1288; Liao, H., Andersson, A.S., Sutherland, D., Petronis, S., Kasemo, B., Thomsen, P., Response of rat osteoblast-like cells to microstructured model surfaces in vitro (2003) Biomaterials, 24, pp. 649-654; Bertrand, P., Jonas, A., Laschewsky, A., Legras, R., Ultrathin polymer coatings by complexation of polyelectrolytes at interfaces: Suitable materials, structure and properties (2000) Macromol Rapid Commun, 21, pp. 319-348; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Sano, M., Lvov, Y., Kunitake, T., Formation of ultrathin polymer layers on solid substrates by means of polymerization-induced epitaxy and alternate adsorption (1996) Ann Rev Mater Sci, 26, pp. 153-187; Laschewsky, A., Ultrathin polymer coatings by self-organization techniques. A critical comparison (1997) Eur Chem Chron, 2, pp. 13-24; Park, S.Y., Barrett, C.J., Rubner, M.F., Mayes, A.M., Anomalous adsorption of polyelectrolyte layers (2001) Macromolecules, 34, pp. 3384-3388; Sullivan, D.M., Bruening, M.L., Ultrathin, ion-selective polyimide membranes prepared from layered polyelectrolytes (2001) J Am Chem Soc, 123, pp. 11805-11806; Chluba, J., Voegel, J.C., Decher, G., Erbacher, P., Schaaf, P., Ogier, J., Peptide hormone covalently bound to polyelectrolytes and embedded into multilayer architectures conserving full biological activity (2001) Biomacromolecules, 2, pp. 800-805; Iler, R.K., Multilayers of colloidal particles (1966) J Colloid Interface Sci, 21, pp. 569-594; Decher, G., Hong, J.D., Buildup of ultrathin multilayer films by a self-assembly process: II. Consecutive adsorption of anionic and cationic bipolar amphiphiles and polyelectrolytes on charged surfaces (1991) Ber Bunsenges Phys Chem, 95, pp. 1430-1434; Decher, G., Fuzzy nanoassemblies: Toward layered polymeric multicomposites (1997) Science, 277, pp. 1232-1237; Lvov, Y., Decher, G., Moehwald, H., Assembly, structural characterization, and thermal behavior of layer-by-layer deposited ultrathin films of poly(vinyl sulfate) and poly(allylamine) (1993) Langmuir, 9, pp. 481-486; Lvov, Y., Haas, H., Decher, G., Moehwald, H., Mikhailov, A., Mtchedlishvily, B., Morgunova, E., Vainshtein, B.S., Successive deposition of alternate layers of polyelectrolytes and a charged virus (1994) Langmuir, 10, pp. 4232-4236; Kleinfeld, E.R., Ferguson, G.S., Stepwise formation of multilayered nanostructural films from macromolecular precursors (1994) Science, 265, pp. 370-373; Hong, D., Lowack, K., Schmitt, J., Decher, G., Layer-by-layer deposited multilayer assemblies of polyelectrolytes and proteins: From ultrathin films to protein arrays (1993) Progr Colloid Polym Sci, 93, pp. 98-102; Schmitt, J., Grunewald, T., Decher, G., Pershan, P.S., Krajer, K., Loesche, M., Internal structure of layer-by-layer adsorbed poly-electrolyte films: A neutron and X-ray reflectivity study (1993) Macromolecules, 26, pp. 7058-7063; Korneev, D., Lvov, Y., Decher, G., Schmitt, J., Yaradaikin, S., Neutron reflectivity analysis of self-assembled film super lattices with alternate layers of deuterated and hydrogenated polystyrenesulfonate and polyallylamine (1995) Physica B, 213-214, pp. 954-956; Zhu, H., Ji, J., Tan, Q., Barbosa, M.A., Shen, J., Surface engineering of poly (DL-lactide) via electrostatic self-assembly of extracellular matrix-like molecules (2003) Biomacromolecules, 4, pp. 378-386; Zhu, Y., Gao, C., He, T., Liu, X., Shen, J., Layer-by-layer assembly to modify poly(1-lactic acid) surface toward improving its cytocompatibility to human endothelial cells (2003) Biomacromolecules, 4, pp. 446-452; Miko, A.G., Sarakinos, G., Vacanti, J.P., Langer, R.S., Cima, L.G., Biocompatible polymer membranes and methods of preparation of three dimensional membrane structures. U. S. Patent No. 5,514378; 1996Instructions: BCA Protein Assay Reagent Kit 23227, , Pierce; Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., Measurement of protein using bicinchoninic acid (1985) Anal Biochem, 150, pp. 76-85; (1998) Product Information: DNA Quantitation Kit Fluorescence Assay (DNA-QF), , SIGMA; West, D.C., Sattar, A., Kumar, S., A simplified in situ solubilization procedure for the determination of DNA and cell number in tissue cultured mammalian cells (1985) Anal Biochem, 147 (2), pp. 289-295; Mosmann, T., Rapid colorimetric assay for cellular growth and survival: Application to proliferation and cytotoxicity assays (1983) J Immunol Methods, 65, pp. 55-63; Zund, G., Ye, Q., Hoerstrup, S.P., Schoeberlein, A., Schmid, A.C., Grunenfelder, J., Vogt, P., Turina, M., Tissue engineering in cardiovascular surgery: MTT, a rapid and reliable quantitative method to assess the optimal human cell seeding on polymeric meshes (1999) Eur J Cardio-thoracic Surg, 15, pp. 519-524
Keywords: 3T3 Cells; Absorbable Implants; Activation analysis; animal cell; Animals; article; Biodegradation; Biomedical engineering; cell activity; cell adhesion; Cell Division; cell growth; cell level; cell protein; cell structure; cell surface; Cell-material interactions; Cells; Coating techniques; DNA; DNA content; Drug products; Electrostatics; ethylene derivative; extracellular matrix; gelatin; Gelation; Growth (materials); Kinetics; macromolecule; materials testing; Mice; Microscopy, Confocal; mouse; nonhuman; osteoblast; Osteoblast growth; Osteoblast testing; Osteoblasts; polyelectrolyte; Polyelectrolytes; Polyesters; Polyethyleneimine; polylactide; polymer; protein assembly; Proteins; Surface modification; Tissue; Tissue engineering

Ultrastructural comparison of dissolution and apatite precipitation on hydroxyapatite and silicon-substituted hydroxyapatite in vitro and in vivo - Porter, A.E.; Botelho, C.M.; Lopes, M.A.; Santos, J.D.; Best, S.M.; Bonfield, W. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2004)
Recent histological studies have demonstrated that the substitution of silicate ions into hydroxyapatite (HA) significantly increases the rate of bone apposition to HA implants. The enhanced bioactivity of silicon-substituted HA (Si-HA) over pure HA has been attributed to the effect of silicate ions in accelerating dissolution. In the present study, high-resolution transmission electron microscopy (HR-TEM) was employed to compare dissolution of HA and Si-HA in an acellular simulated body fluid (SBF) to dissolution in an in vivo model. HR-TEM observations confirmed a difference in morphology of apatite precipitates in vivo and in SBF: apatite deposits were platelike in vivo and nodular in SBF. Compositional mapping suggested that preferential dissolution of silicon from the implant promotes the nucleation of carbonate apatite around the implant. The in vivo findings illustrated an absence of dissolution at the bone-HA or Si-HA interface, whereas dissolution was extensive from within the implant. The amount of dissolution in acellular SBF was similar to dissolution from within the implant, although the site at which the dissolution nucleates was different: dissolution predominates at the crystallite surfaces in SBF, whereas grain boundary dissolution predominates in vivo. These findings suggest that proteins in the in vivo milieu modify the processes of dissolution from the implant. © 2004 Wiley Periodicals, Inc.
Cited By (since 1996): 48Export Date: 21 November 2012Source: ScopusCODEN: JBMRCPubMed ID: 15162409Language of Original Document: EnglishCorrespondence Address: Porter, A.E.; Dept. of Mat. Science and Metallurgy, University of Cambridge, Pembroke Street, Cambridge, CB2 3QZ, United Kingdom; email: aep30@cam.ac.ukChemicals/CAS: apatite, 64476-38-6; carbonic acid, 3812-32-6, 463-79-6; hydroxyapatite, 1306-06-5, 51198-94-8; silicon, 7440-21-3; Biocompatible Materials; Durapatite, 1306-06-5; Silicon, 7440-21-3References: Porter, A.E., Best, S.M., Bonfield, W., Ultrastructural comparison of hydroxyapatite and silicon-substituted hydroxyapatite for biomedical applications (2003) J Biomed Mater Res, 68 A, pp. 133-141;Patel, N., Gibson, I.R., Hing, K.A., Best, S.M., Revell, P.A., Bonfield, W., A comparative study on the in vivo behaviour of hydroxyapatite and silicon substituted hydroxyapatite granules (2002) J Mater Sci Mater Med, 13, pp. 1199-1206; Porter, A.E., Patel, N., Skepper, J.N.S., Best, S.M., Bonfield, W., Comparison of in vivo dissolution processes in hydroxyapatite and silicon-hydroxyapatite bioceramics (2003) Biomaterials, 24, pp. 4609-4620; Weng, J., Liu, Q., Wolke, J.G.C., Zhang, X., De Groot, K., Formation and characteristics of the apatite layer on plasma-sprayed hydroxyapatite coatings in simulated body fluid (1995) Biomaterials, 18, pp. 1027-1035; Doi, Y., Shibutani, T., Moriwake, Y., Kajimoto, T., Iwayama, Y., Sintered carbonate apatites as bioresorbable bone substitutes (1997) J Biomed Mater Res, 39, pp. 603-610; Schepers, E., Declercq, M., Ducheyne, P., Kempeneers, R., Bioactive glass particulate material as a filler for bone lesions (1991) J Oral Rehab, 18, pp. 439-452; Ducheyne, P., Qiu, Q., Bioactive ceramics: The effect of surface reactivity on bone formation and bone cell function (1999) Biomaterials, 20, pp. 2287-2303; Ducheyne, P., Radin, S., King, L., The effect of calcium-phosphate ceramic composition and structure on in vitro behaviour. I. Dissolution (1993) J Biomed Mater Res, 27, pp. 25-34; Kukubo, T., Kushitani, H., Sakka, S., Solutions able to reproduce in vivo surface-structure changes in bioactive glass-ceramic A-W (1990) J Biomed Mater Res, 24, pp. 721-734; Radin, S.R., Ducheyne, P., The effect of calcium phosphate ceramic composition and structure on in vitro behavior. II. Precipitation (1993) J Biomed Mater Res, 27, pp. 35-45; Gibson, I.R., Hing, K.A., Best, S.M., Bonfield, W., Enhanced in vitro cell activity and surface apatite layer formation on novel silicon-substituted hydroxyapatites (1999) 12th International Symposium on Ceramics in Medicine, pp. 191-194. , Ohgushi H, Hastings GW, Yoshikawa T, editors. Nara, Japan. World Scientific; Fujibayashi, S., Neo, M., Kim, H.-M., Kokubo, T., Nakamura, T., A comparative study between in vivo bone ingrowth and in vitro apatite formation on Na 2-CaO-SiO 2 glasses (2003) Biomaterials, 24, pp. 1349-1356; Porter, A.E., Patel, N., Skepper, J.N., Best, S.M., Bonfield, W., Effect of sintered silicate-substituted hydroxyapatite on remodelling processes at the bone-implant interface (2003) Biomaterials, 25, pp. 3303-3314; Leng, Y., Chen, J., Qu, S., TEM study of calcium phosphate precipitation on HA/TCP ceramics (2003) Biomaterials, 24, pp. 2125-2131; Akao, M., Aoki, H., Kato, K., Mechanical properties of sintered hydroxyapatite for prosthetic applications (1981) J Mater Sci, 28, p. 809; Gibson, I.R., Best, S.M., Bonfield, W., Chemical characterization of silicon-substituted hydroxyapatite (1999) J Biomed Mater Res, 44, pp. 422-428; Rey, C., Calcium phosphates for medical applications (1998) Calcium Phosphates in Biological and Industrial Systems, pp. 217-251. , Amjad Z, editor. Kluwer Academic: Boston; Tanizawa, Y., Suzuki, T., Effects of silica ions on the formation and transformation of calcium phosphates in neutral aqueous solutions (1995) J Chem Soc Faraday Trans, 91, pp. 3499-3503; Damen, J.J.M., Ten Cate, J.M., Silica-induced precipitation of calcium phosphate in the presence of inhibitors of hydroxyapatite formation (1992) J Dent Res, 71, pp. 453-457; Botelho, C.M., Lopes, M.A., Gibson, I.R., Best, S.M., Santos, J.D., Structural analysis of Si-substituted hydroxyapatite: Zeta potential and X-ray photoelectron spectroscopy (XPS) (2002) J Mater Sci Mater Med, 13, pp. 1123-1127; Carlisle, E.M., Silicon (1975) Nutr Rev, 33, pp. 257-260; Termine, J.D., Eanes, E.D., Conn, K.M., Phosphoprotein modulation of apatite crystallization (1980) Calcif Tissue Int, 31, pp. 247-251; Combes, C., Rey, C., Adsorption of proteins and calcium phosphate materials bioactivity (2002) Biomaterials, 23, pp. 2817-2823; Horbett, T.A., Proteins at interfaces - An overview (1995) ACS Symp Ser, pp. 602-623
Keywords: Apatite; article; Bioactivity; Biocompatible Materials; body fluid; carbonic acid; comparative study; Composition; Dissolution; Durapatite; histology; hydroxyapatite; implant; Implants (surgical); in vitro study; in vivo study; Interfaces (materials); Microscopy, Electron; Microscopy, Electron, Scanning; morphology; precipitation; Precipitation (chemical); Silicon; Simulated body fluid; Simulated body fluids (SBF); simulation; transmission electron microscopy; ultrastructure

XRD and FT-IR characterisation of hydroxyapatite sputtered films on titanium - Silva, R.A.; Sousa, M.; Monteiro, F.J.; Barrai, R.; Lopes, M.A. (Transactions - 7th World Biomaterials CongressTrans. World Biomater. Congr., 2004)
XRD and FT-IR were used to characterize hydroxyapatite (HA) films, which were prepared using rf sputtering. The morphology of the sample films was analyzed using SEM. From the FT-IR spectrum, sputtered HA films showed structural changes, namely the decrease of the strength of the liberational mode of OH group, indicating the presence of a poorly crystalline phase. XRD results of films obtained at 500 W and 400 W showed that the crystallinity of the 500 W 4h e 2h samples was low, just showing a very incipient degree of crystalline structural structural arrangement, while in the 400 W-4h and 2h samples there was no crystalline structure, with only a slight diffraction of the 002 and 301 HA planes.
Conference code: 64310Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Silva, R.A.; Inst. Sup. de Engenharia do Porto, Rua Dr.Antonio Bernardino A., 431, 4200- 072 Porto, Portugal; email: ras@isep.ipp.ptReferences: Wolke, J.G.C., (1998) J.Biomed. Mat. Res, 39, pp. 524-530;Silva, R.A., Proceedings of Bioceramics 16, , to be published
Keywords: Absorption bands; Adsorption; Bioactive films; Biomaterials; Bone; crystal structure; Crystallinity; Deposition; Fourier transform infrared spectroscopy; hydroxyapatite; Hydroxyapatite films; morphology; Scanning electron microscopy; Sintering; Sputtering; Surface topography; Thin films; Titanium; X ray diffraction analysis

Constructing thromboresistant surface on biomedical stainless steel via layer-by-layer deposition anticoagulant - Tan, Q.; Ji, J.; Barbosa, M.A.; Fonseca, C.; Shen, J. (BiomaterialsBiomaterials, 2003)
Multilayer films consisting of polyethylenimine (PEI) and heparin were successfully prepared on biomedical 316L stainless steel surface via electrostatic self-assembly (ESA) of the PEI and heparin. The process of ESA of PEI/heparin was monitored by static contact angle, electrochemical impedance spectroscopy (EIS), reflection adsorption spectroscopy and X-ray photoelectron spectroscopy data. The contact angle and EIS data revealed that the multilayer coating was stable in Tris-HCl (pH 7.35) buffer solution for 21 days. The static platelet adhesion and static clotting time experiments indicated that the PEI/heparin-deposited stainless steel could resist the platelet adhesion and prolong the static clotting time effectively. Such an easy processing and shape-independent method may have good potential for surface modification of cardiovascular devices. © 2003 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 67Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(03)00363-6PubMed ID: 12951013Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, Hangzhou 310027, China; email: jianji@mail.hz.zj.cnChemicals/CAS: heparin, 37187-54-5, 8057-48-5, 8065-01-8, 9005-48-5; polyethyleneimine, 74913-72-7; stainless steel, 12597-68-1; trometamol, 1185-53-1, 77-86-1; Anticoagulants; Coated Materials, Biocompatible; Heparin, 9005-49-6; Polyethyleneimine, 9002-98-6; Stainless Steel, 12597-68-1Manufacturers: AldrichReferences: Bertrand, P., Jonas, A., Laschewsky, A., Legras, R., Ultrathin polymer coating by complexation of polyelectrolytes at interfaces: Suitable materials, structure and properties (2000) Macromol Rapid Commun, 21, pp. 319-348;Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Sano, M., Lvov, Y., Kunitake, T., (1996) Annu Rev Mater Sci, 26, pp. 153-187; Laschewsky, A., (1997) Eur Chem Chron ECC, 2, pp. 13-24; Picart, C., Lavalle, Ph., Hubert, P., Cuisnier, Fj., Decher, G., Schaaf, P., Voegel, J.C., Buildup mechanism for poly (L-lysine)/hyaluronic acid films onto a solid surface (2001) Langmuir, 17, pp. 7414-7424; Houska, M., Brynda, E., Interactions of proteins with polyelectrolytes at solid/liquid interfaces: Sequential adsorption of albumin and heparin (1997) J Colloid Interface Sci, 188, pp. 243-250; Brynda, E., Houska, M., Multiple alternating molecular layers of albumin and heparin on solid surfaces (1996) J Colloid Interface Sci, 183, pp. 18-25; Thomann, U.I., Uggowitzer, P.J., Wear-corrosion behavior of biocompatible austenitic stainless steels (2000) Wear, 239, pp. 48-58; Cheatham, J., Improved stents for pediatric applications (2001) Prog Pediatr Cardiol, 14, pp. 95-115; Donachie, M., Biomedical alloys (1998) Adv Mater Process, 154, pp. 63-65; Decher, G., Fuzzy nanoassemblies: Toward layered polymeric multicomposites (1997) Science, 277, pp. 1232-1237; Raposo, M., Pontes, R.S., Mattoso, L.H.C., Oliveira, O.N., Kinetics of adsorption of poly (o-methoxyaniline) self-assembled films (1997) Macromolecules, 30, pp. 6095-6101; Vov, Y.L., Rusling, J., Thomsen, D.L., Papadimitrakopoulos, F., Kawakami, T., Kunitake, T., High-speed multilayer film assembly by alternate adsorption of silica nanoparticles and linear polycation (1998) Chem Commun, 11, pp. 1229-1230; Lowack, K., Helm, C.A., Controlling the self-assembly process of polyelectrolyte multilayers (1998) Macromolecules, 31, pp. 823-833; Cheng, Z., Cheng, L., Dong, S., Yang, X., Formation and characterization of heteropolyacid/polycation multilayer films on gold electrode (2001) J Electrochem Soc, 148, p. 227
Keywords: 316L stainless steel; Adhesion; Adsorption; anticoagulant agent; Anticoagulants; aqueous solution; article; Biocompatibility; biomaterial; Biomaterials; blood clotting time; Blood Platelets; Blood-compatibility; buffer; Coated Materials, Biocompatible; coating; Coatings; Contact angle; controlled study; Deposition; device; electricity; Electrochemical impedance spectroscopy; electrochemistry; Electrostatics; heparin; human; human cell; Humans; implant; Layer-by-layer; material coating; materials testing; Multilayers; Organic polymers; pH; Platelet Adhesiveness; Polyethyleneimine; priority journal; reflection adsorption spectroscopy; Self assembly; Spectroscopy; Stainless steel; Surface Properties; surface property; Surfaces; thrombocyte adhesion; Thromboresistant surfaces; trometamol; X ray photoelectron spectroscopy

Development of foetal and neonatal simulators at the University of Porto - van Meurs, W.L.; Sá Couto, P.M.; Sá Couto, C.D.; Bernardes, J.F.; Ayres-de-Campos, D. (Medical Education, SupplementMed. Educ. Suppl., 2003)
Background: Human error can be expected to play a significant role in adverse outcomes in perinatal acute care. In acute care of the adult, simulator based training is recommended and used to improve patient safety. Aims: Our general goal is to develop model-driven foetal and neonatal educational simulators and curricula. The specific objectives of this paper are to introduce the reader to the perinatal acute care context and simulator design considerations, as well as to give initial results and describe ongoing developments. A brief description of adult simulators and simulation engines is followed by a more detailed description of a foetal distress simulator (FDS) and of models for a neonatal simulator developed at the University of Porto. Ongoing developments involve the modelling of foetal baroreflexes, the effect of uterine contractions, and an adapted method for estimating foetal heart rate variability parameters. Results: We present FDS simulation results reflecting the changes in oxygen supply to the foetus and the foetal heart rate in response to a reduction in uterine blood flow. We also present a structural diagram of a model for the educational simulation of congenital heart disease and preliminary simulation results reflecting a patent ductus arteriosus. Conclusion: We expect that, after initial clinical and educational validation, the presented models and simulators will play a role in simulator-based educational programmes contributing to increased perinatal safety.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: MESECPubMed ID: 14641636Language of Original Document: EnglishCorrespondence Address: Van Meurs, W.L.; INEB - Inst. de Engenharia Biomedica, Lab. de Sinal e Imagem Biomedica, Edificio I-Poente, Rua Roberto Prias, s/n, 4200-465 Porto, Portugal; email: wvanmeurs@ineb.up.ptChemicals/CAS: oxygen, 7782-44-7References: Kohn, L.T., Corrigan, J.M., Donaldson, M.S., (2000) To Err Is Human, Building a Safer Health Care System, , Washington, DC: National Academic Press;Denson, J.S., Abrahamson, S., A computer-controlled patient simulator (1969) JAMA, 208, pp. 504-508; Gaba, D.M., DeAnda, A., A comprehensive anesthesia simulation environment. Re-creating the operating room for research and training (1988) Anesthesiology, 69, pp. 387-394; Good, M.L., Gravenstein, J.S., Anesthesia simulators and training devices (1989) Int Anesthesiol Clin, 27, pp. 161-168; Gaba, D., Howard, S., Fish, K., Smith, B., Sowb, Y., Simulation-based training in anesthesia crisis resource management (ACRM): A decade of experience (2001) Simulation Gaming, 32, pp. 175-193; Gordon, J.A., 'Practicing' medicine without risk: Students' and educators' responses to high-fidelity patient simulation (2001) Acad Med, 76, pp. 469-472; Ma, O., Simulation saves lives (2001) Newsletter of the American Society of Anesthesiologists, , Park Ridge: American Society of Anesthesiologists; October; Van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit, 13, pp. 317-324; Van Meurs, W.L., Nikkelen, E., Good, M.L., Pharmacokinetic-pharmacodynamic model for educational simulations (1998) IEEE Trans Biomed Eng, 45, pp. 582-590; Öhrn, M.A.K., Van Oostrom, J.H., Van Meurs, W.L., A comparison of traditional textbook and interactive computer learning of neuromuscular block (1997) Anesth Analg, 84, pp. 657-661; Euliano, T.Y., Caton, D., Van Meurs, W.L., Good, M.L., Modeling obstetric cardiovascular physiology on a full-scale patient simulator (1997) J Clin Monit, 13, pp. 293-297; Sá Couto, P.M., Van Meurs, W.L., Bernardes, J.F., Marques De Sá, J.P., Goodwin, J.A., Mathematical model for educational simulation of the oxygen delivery to the fetus (2002) Cont Eng Prac, 10, pp. 59-66; Sá Couto, P.M., Van Meurs, W.L., Bernardes, J.F., Marques De Sá, J.P., Goodwin, J.A., Combined model-driven and rule-based approach for educational simulation of fetal heart rate (2002) BIOSIGNAL 2002. Proceedings of the 16th Biennial International Conference of the European Association for Speech, Signal and Image Processing (EURASIP), 26-28 June 2002, Brno, Czech Republic, pp. 400-402. , Jan J, Kozumplík J, Provazník I, eds. Brno: Vutium Press; Itskovitz, J., LaGamma, E.F., Rudolph, A.M., Heart rate and blood pressure responses to umbilical cord compression in fetal lambs with special references to the mechanism of variable deceleration (1983) Am J Obstet Gynecol, 147, pp. 451-457; Lee, S.T., Hon, E.H., Fetal hemodynamic response to umbilical cord compression (1963) J Obstet Gynecol, 22, pp. 553-562; Goodlin, R.C., Lowe, E.W., A functional umbilical cord occlusion heart rate pattern - The significance of overshoot (1974) Obstet Gynecol, 43, pp. 22-30; Scheffs, J., Vasicka, A., Li, C., Solomon, N., Siler, W., Uterine blood flow during labor (1971) Obstet Gynecol, 38, pp. 15-24; Brotanek, V., Hendricks, C.H., Yoshida, T., Importance of changes in uterine blood flow in initiation of labor (1969) Am J Obstet Gynecol, 105, pp. 535-546; Butler, L.A., Longo, L.D., Power, G.G., Placental blood flows and oxygen transfer during uterine contractions: A mathematical model (1976) J Theor Biol, 61, pp. 81-95; Felgueiras, C., Marques De Sá, J.P., Bernardes, J., Gama, S., Classification of foetal heart rate sequences based on fractal features (1998) Med Biol Eng Comput, 36, pp. 197-201; Sá Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Graphical and mathematical representation of congenital heart disease (2002) Proceedings of the SESAM Annual Meeting, 10-11 May 2002; Centro de Entrenamiento en Situaciones Críticas, Santander, Spain, p. 18; Beneken, J.E.W., (1965) A Mathematical Approach to Cardiovascular Function: The Uncontrolled Human System, , PhD dissertation. Utrecht, The Netherlands: Rijksuniversiteit Utrecht; Huikeshoven, F., Coleman, T.G., Jongsma, H.W., Mathematical model of the fetal cardiovascular system: The uncontrolled case (1980) Am J Physiol, 239, pp. R317-25; Klaus, M.H., Fanaroff, A.A., (2001) Care of the High-Risk Neonate, 5th Edn., , Philadelphia: WB Saunders
Keywords: article; audiovisual equipment; blackstarPatient simulation; clinical competence; Clinical competence/blackstarstandards/economics; competence; Curriculum; Education, Medical, Undergraduate; Education, medical, undergraduate/blackstarmethods; Equipment Safety; fetus distress; human; Humans; Manikins; medical education; model; oxygen; Patient Simulation; perinatal care; Perinatal care/ blackstarstandards/methods; Portugal; safety; simulator; training

Dissolution studies of hydroxyapatite and glass-reinforced hydroxyapatite ceramics - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J.; Prado da Silva, M.H. (Materials CharacterizationMater Charact, 2003)
In the continuous agitation assays, glass-reinforced hydroxyapatite (GR-HA) was shown to form a calcium phosphate (CaP) layer, but hydroxyapatite (HA) only formed dispersed precipitates. The formation of this layer was first detected on the GR-HA with a 7.5% glass addition (7.5 GR-HA) after only 3 days of immersion in simulated body fluid (SBF). The time required for layer formation decreased as the amount of glass added to the HA increased. The dissolution rate of the materials followed a similar pattern, i.e. the dissolution rate for GR-HA was higher than for HA, and increased with the addition of glass. The immersion of 7.5 GR-HA in water showed almost linear dissolution kinetics over the immersion periods (3, 7, 15, 30 and 60 days). The concentration of calcium ions in solution and the scanning electron microscopy (SEM) analysis of the 7.5 GR-HA specimens immersed in water and in SBF revealed a clear competition between the material dissolution and the precipitation of a CaP phase. Fourier transformed infrared spectroscopy with alternated total reflectance (FTIR-ATR) analysis indicated that the CaP phase that formed during longer immersion times (30 and 60 days) could be a carbonate-substituted CaP precipitate. As expected from previous work, the GR-HA behavior in terms of its in vitro bioactivity is higher than HA because a homogeneous CaP layer is formed and the precipitation occurs faster. From the dissolution test and in accordance with the chemical composition of the samples, GR-HA was more soluble than HA. © 2003 Elsevier Inc. All rights reserved.
Conference code: 61615Cited By (since 1996): 15Export Date: 21 November 2012Source: ScopusCODEN: MACHEdoi: 10.1016/S1044-5803(03)00092-5Language of Original Document: EnglishCorrespondence Address: Prado da Silva, M.H.; DEMP, UFC, Campus PICI, Bl. 714, Fortaleza, CE 60455-760, Brazil; email: mhprado@dem.ufc.brReferences: Barinov, S.M., Baschenko, Y.V., Application of ceramic composites as implants: Result and problem (1992) Bioceramics and the Human Body, pp. 206-210. , A. Ravaglioli, & A. Krajewski. United Kingdom: Elsevier;Nishihara, K., Studies on peri-root tissue formation around new type artificial root made of dense hydroxyapatite (1993) Clin. Mater., 12, pp. 159-167; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tensions, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J. Biomed. Mater. Res., 45, pp. 370-375; Santos, J.D., Silva, P.L., Knowles, J.C., Talal, S., Monteiro, F.J., Reinforcement of hydroxyapatite by adding P 2O 5-CaO glasses with Na 2O, K 2O, MgO (1996) J. Mater. Sci. Mater. Med., 7, pp. 187-189; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of effects of glass on response of osteosarcoma cells to plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings (1999) J. Biomed. Mater. Res., 47, pp. 603-611; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P 2O 5 glass hydroxyapatite double-layer plasma-sprayed coating: In vitro bioactivity evaluation (1999) J. Biomed. Mater. Res., 45, pp. 376-383; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J. Biomed. Mater. Res., 54, pp. 463-469; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J. Biomed. Mater. Res., 41, pp. 649-656; Kokubo, T., Ito, S., Huang, Z.T., Hayashi, T., Sakka, S., Ca, P-rich layer formed on high-strength bioactive glass-ceramic A-W (1990) J. Biomed. Mater. Res., 24, pp. 331-343; Kokubo, T., Kushitani, H., Kitsugi, T., Yamamuro, T., Solution able to reproduce in vivo surface-structure changes of bioactive glass-ceramic A-W (1990) J. Biomed. Mater. Res., 24, pp. 721-734; Klein, C.P.A.T., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., Features of calcium phosphate plasma-sprayed coatings: An in vitro study (1994) J. Biomed. Mater. Res., 28, pp. 961-967; Klein, C.P.A.T., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., Calcium phosphate plasma-sprayed coatings and their stability: An in vivo study (1994) J. Biomed. Mater. Res., 28, pp. 909-917; Kokubo, T., Kushitani, H., Ohtsuki, C., Sakka, S., Yamamuro, T., Chemical reaction of bioactive glass and glass-ceramics with a simulated body fluid (1992) J. Mater. Sci. Mater. Med., 3, pp. 79-83; Zhang, H., Li, S., Yan, Y., Dissolution behaviour of hydroxyapatite powder in hydrothermal solution (2001) Ceram. Int., 27, pp. 451-454; LeGeros, R.Z., LeGeros, J.P., Calcium phosphate biomaterials in medical applications (1996) Bioceramics, 9, pp. 7-10. , T. Kokubo, T. Nakamura, & F. Miyaji. Otsu, Japan: Elsevier; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Gibson, I.R., Knowles, J.C., Adsorption and release studies of sodium ampicillin from hydroxyapatite and glass-reinforced hydroxyapatite composites (2001) Biomaterials, 22, pp. 1393-1400; Langenbucher, F., Benz, D., Kürth, W., Möller, H., Otz, M., Standardized flow-cell method as an alternative to existing pharmacopoeial dissolution testing (1989) Pharm. Ind., 51 (11), pp. 1276-1281; Kokubo, T., (1990) CRC Handbook of Bioactive Ceramics, 1, p. 41. , T. Yamamuro, L.L. Hench, & J. Wilson. Boca Raton (FL): CRC Press; International Standard ISO/FDIS 10993-14, Biological evaluation of medical devices: Part 14 (2001) Identification and Quantification of Degradation Products from Ceramics
Keywords: Ceramic materials; Dissolution; glass; Glass-reinforced hydroxyapatite; hydroxyapatite; Immersion times; Scanning electron microscopy

Effect of heat treatment on relative content of β-Ca 2P 2O 7 crystalline phase in calcium phosphate glass-ceramics - Li, Y.; Weng, W.; Du, P.; Shen, G.; Han, G.; Santos, J.D.; Lopes, A.M. (Kuei Suan Jen Hsueh Pao/ Journal of the Chinese Ceramic SocietyKuei Suan Jen Hsueh Pao, 2003)
The 3Na 2O-12TiO 2-57CaO-28P 2O 5 glass was heat-treated to form glass-ceramics under different conditions. The relationships between the heat-treatment conditions and the content of β-Ca 2P 2O 7 in the glass-ceramics, bioactivity of the glass-ceramics were investigated. The experimental results show that the glass-ceramics contain crystalline phases of β-Ca 2P 2O 7, CaTi 4(PO 4) 6, NaTi 2(PO 4) 3 and TiP 2O 7 after heat-treatment, in which β-Ca 2P 2O 7 crystalline phase is a dominant one; the content of β-Ca 2P 2O 7 crystalline phase in the glass-ceramics increases with the increase of nucleation temperature and time; and the glass-ceramics with more β-Ca 2P 2O 7 crystalline phase has a better bioactivity. The role of heat-treatment in increasing the content of β-Ca 2P 2O 7 crystalline phase in the glass-ceramics is attributed to the crystallization of β-Ca 2P 2O 7 involved in the simultaneous occurrence of the glass phase separation and nucleation processes. Due to the better ability of β-Ca 2P 2O 7 in promoting bioactivity, the glass-ceramics with more β-Ca 2P 2O 7 phase have stronger bioactivity. Therefore, the bioactivity of the glass-ceramics could be changed by heat treatment.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KSYHALanguage of Original Document: ChineseCorrespondence Address: Li, Y.; Dept. of Mat. Sci. and Eng., Zhejiang Univ., Hangzhou 310027, ChinaReferences: Hench, L.L., Bioceramics (1998) J. Am. Ceram. Soc., 81, pp. 1705-1731;Kitsugi, T., Yamamuro, T., Nakamura, T., Four calcium phosphate ceramics as bone substitute for non-weight bearing (1993) Biomaterials, 14, pp. 216-221; Kitsugi, T., Yamamuro, T., Nakamura, T., Transmission electron microscopy observations at the interface of bone and four types of calcium phosphate ceramics with different calcium/phosphorus molar ratios (1995) Biomaterials, 16, pp. 1101-1107; Yu, B., Liang, K., Gu, S., (2002) J. Chin. Ceram. Soc., 30 (1), pp. 77-80; Kasuga, T., Sawada, M., Nogami, M., Biomaterials, bioactive ceramics prepared by sintering and crystallization of calcium phosphate invert glasses (1999) Biomaterials, 20, pp. 1415-1420; Zhang, Y., Santos, J.D., Microstructural characterization and in vitro apatite formation of CaO-P 2O 5-TiO 2MgO-Na 2O glass-ceramics (2001) J. Eur. Ceram. Soc., 21, pp. 169-175; Kokubo, T., Ito, S., Sakka, S., Formation of a high strength bioactive glass ceramic in the system MgO-CaO-SiO 2-P 2O 5 (1986) J. Mater. Sci., 21, pp. 536-540; Hosono, H., Zhang, Z., Abe, Y., Porous glass-ceramics in the CaO-TiO 2-P 2O 5 system (1989) J. Am. Ceram. Soc., 72, pp. 1587-1589; Zhang, Y., Santos, J.D., Crystallization and microstructure analysis of calcium phosphate-based glass ceramics for biomedical applications (2000) J. Non-Cryst. Solids, 272, pp. 14-21; Li, Y., Study on bioactive glass-ceramics in Na 2O-TiO 2-CaO-P 2O 5 system (2001), Chinese source, Dissertation, Hangzhou: Zhejiang UniversityKokubo, T., Surface chemistry of bioactive glass-ceramics (1990) J. Non.-Cryst. Solids, 120, pp. 138-151
Keywords: Bioactivity; Calcium Compounds; calcium phosphate; Crystalline materials; Crystalline phase; Crystallization; Glass ceramics; Glass-ceramics; Heat treatment; Nucleation; Phase separation; Phosphates

In vitro degradation studies of calcium phosphate glass ceramics prepared by controlled crystallization - Dias, A.G.; Lopes, M.A.; Gibson, I.R.; Santos, J.D. (Journal of Non-Crystalline SolidsJ Non Cryst Solids, 2003)
Calcium phosphate glass ceramics with incorporation of small additions of two nucleating agents, MgO and K 2O were prepared in the metaphosphate and pyrophosphate region, using an appropriate two-step heat treatment of controlled crystallization defined by differential thermal analysis results. Identification and quantification of crystalline phases precipitated from the calcium phosphate glass were performed using X-ray diffraction and Rietveld analysis. The β-Ca 2P 2O 7 (β-DCP), KCa(PO 3) 3, β-Ca(PO 3) 2 and Ca 4P 6O 19 phases were detected in the glass ceramics. In order to evaluate the degradation of the glass ceramics prepared, degradation studies were carried out during 42 days in Tris-HCl solution at 37 °C, pH 7.4, using granules in the range of 355-415 μm. The materials presented a weight loss ranging up to 12%. The ions leached during the immersion mainly originated from the KCa(PO 3) 3 phase, probably due to the presence of K + ion in the calcium metaphosphate, and the residual glassy phase. The structural changes at the surface of materials during degradation have been analyzed by Fourier transform infrared spectroscopy and X-ray diffraction. Results showed that significant surface changes occurred with immersion time, with the decrease of KCa(PO 3) 3, β-Ca 2P 2O 7 and β-Ca(PO 3) 2 phases occurring at different periods of immersion. This study has demonstrated an easy way to prepared calcium phosphate materials with specific calcium phosphate phases and crystallization, and therefore specific degradation rates. © 2003 Elsevier B.V. All rights reserved.
Cited By (since 1996): 28Export Date: 21 November 2012Source: ScopusCODEN: JNCSBdoi: 10.1016/j.jnoncrysol.2003.08.056Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Depto. de Engenharia Metalurgica, Fac. de Engenharia da Univ. do Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Hall, B.K., (1992) Bone, Fracture Repair and Regeneration, 5. , CRC;Vidal, J., Dossa, J., Le Tissu Osseux (1990) Collection: Biologie de l'Appareil Locomoteur, , L. Teot (Ed.); Legeros, R.Z., (1991) Calcium Phosphates in Oral Biology and Medicine, , H.M. Meyers, N.Y. Karger (Eds.); Yamamuro, T., Hench, L.L., Wilson, J., Handbook of Bioactive Ceramics (1990) Bioactive Glasses and Glass Ceramics, 1. , Takao (Ed.), CRC; Hench, L.L., Wilson, J., Wilson, J., Handbook of Bioactive Ceramics (1990) Calcium Phosphate and Hydroxyapatite Ceramics, 2. , Yamamuro T. (Ed.), CRC; Kitsugi, T., Yamamuro, T., Nakamura, T., Oka, M., (1995) Biomaterials, 16, p. 1101; Kasuga, T., Abe, Y., (1999) J. Non-Cryst. Solids, 243, p. 70; Zhang, Y., Santos, J.D., (2000) J. Non-Cryst. Solids, 272, p. 14; Hartmann, P., Vogel, J., Schnabel, B., (1994) J. Non-Cryst. Solids, 176, p. 157; Brow, R.K., (2000) J. Non-Cryst. Solids, 263-264, p. 1; Jones, A.R., Winter, R., Greaves, G.N., Smith, I.H., (2001) J. Non-Cryst. Solids, 293-295, p. 87; Clément, J., Manero, J.M., Planell, J.A., Avila, G., Martínez, S., (1999) J. Mater. Sci.: Mater. Med., 10, p. 729; Zhang, Y., Lopes, M.A., Santos, J.D., (2001) Key Eng. Mater., 192-195, p. 643; Uo, M., Mizuno, M., Kuboki, Y., Makishima, A., Watari, F., (1998) Biomaterials, 19, p. 2277; Franks, K., Abrahams, I., Knowles, J.C., (2000) J. Mater. Sci.: Mater. Med., 11, p. 609; Kasuga, T., Abe, Y., (1998) J. Mater. Res., 13 (12), p. 3357; Franks, K., Abrahams, I., Georgiou, G., Knowles, J.C., (2001) Biomaterials, 22, p. 497; Hill, R.J., Howard, C.J., (1987) J. Appl. Crystallogr., 20, p. 467; Nyquist, R.A., (1997) Handbook of Infrared and Raman Spectra of Inorganic Compounds and Organics Salts (a4 - Volume Set), , Academic Press; Nan, Y., Lee, W.E., James, P.F., (1992) J. Am. Ceram. Soc., 75 (6), p. 1641; Reaney, I.M., James, P.F., Lee, W.E., (1996) J. Am. Ceram. Soc., 79 (7), p. 1934; Shi, W., James, P.F., (1991) Proceedings of a Conference on Physics of Non-crystalline Solids, , University of Cambridge, UK; Kasuga, T., Abe, Y., (1988) Proceedings of the XVIII International Congress on Glass, p. 31. , American Ceramic Society; Chun, S., Na, S.W., Lee, J.H., Chung, J.P., Ryu, I.C., Kim, S.Y., (2002) Key Eng. Mater., 218-220, p. 149
Keywords: Calcium Compounds; Crystallization; Degradation; Differential thermal analysis; Fourier transform infrared spectroscopy; Glass ceramics; Heat treatment; Nucleating agents; Nucleation; X ray diffraction

Surface engineering of poly(DL-lactide) via electrostatic self-assembly of extracellular matrix-like molecules - Zhu, H.; Ji, J.; Tan, Q.; Barbosa, M.A.; Shen, J. (BiomacromoleculesBiomacromolecules, 2003)
We report the development of new biomacromolecule coatings on biodegradable biomaterials based on electrostatic assembly of extracellular matrix-like molecules. Poly(ethylene imine) (PEI) was employed to engineer poly(DL-lactide) (PDL-LA) substrate to obtain a stable positively charged surface. An extracellular matrix- (ECM-) like biomacromolecule, gelatin, was selected as the polyelectrolyte to deposit on the activated PDL-LA substrate via the electrostatic assemble technique. The extracellular matrix-like multilayer on the PDL-LA substrate was investigated by attenuated total reflection (ATR-FTIR), X-ray photoelectron spectrscopy (XPS), contact angle, and atomic force microscopy (AFM). The gradual buildup of the protein layer was investigated by UV-vis spectra, and it was further given a quantitative analysis of the protein layer on the PDL-LA substrate via the radioiodination technique. The stability of the protein layer under aqueous condition was also tested by the radiolabeling method. Chondrocyte was selected as the model system for testing the cell behavior and morphology on modified PDL-LA substrates. The chondrocyte test about cell attachment, proliferation, cell activity and cell morphology by SEM, and confocal laser scanning microscopy (CLSM) investigation on extracellular matrix-like multilayer modified PDL-LA substrate was shown to promote chondrocyte attachment and growth. Comparing conventional coating methods, polyelectrolyte multiplayers are easy and stable to prepare. It may be a good choice for the modification of 3-D scaffolds used in tissue engineering. These very flexible systems allow broad medical applications for drug delivery and tissue engineering.
Cited By (since 1996): 48Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm025773pPubMed ID: 12625735Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science/Eng., Zhejing University, Hangzhou 310027, China; email: jianji@mail.hz.zj.cnChemicals/CAS: gelatin, 9000-70-8; polyethyleneimine, 74913-72-7; polylactide, 26680-10-4; poly(lactide), 26969-66-4; PolyestersTradenames: AXIOVERT 200, Zeiss; ESCA LAB 200A, VG; Radiance 2100, Biorad; Shimadzu UV-1201, Shimadzu; SPA 400, Seiko; Vectro 22, BrukerManufacturers: Biorad; Bruker; Seiko; Shimadzu; VG; ZeissReferences: Sittinger, M., Perka, C., Schutz, O., Haupl, T., Burmester, G.R.Z., (1999) Rheumatol., 58, pp. 130-135;Kim, B.S., Mooney, D.J., (1998) Trends Biotechnol., 16, p. 224; Bertrand, P., Jonas, A., Laschewsky, A., Legras, R., (2000) Macromol. Rapid Commun., 21, p. 319; Ulman, A., (1996) Chem. Rev., 96, p. 1533; Sano, M., Lvov, Y., Kunitake, T., (1996) Annu. Rev. Mater. Sci., 26, pp. 153-187; Laschewsky, A., (1997) Eur. Chem. Chronicle ECC, 2, pp. 13-24; Chluba, J., Voegel, J.C., Decher, G., Erbacher, P., Schaaf, P., Ogier, J., (2001) Biomacromolecules., 2, pp. 800-805; Iler, R., (1966) J. Colloid Interface Sci., 21, p. 569; Fromhertz, P., (1980) Electron Microscopy at Molecular Dimension, p. 338. , Baumeister, W., Ed.; Springer-Verlag: Berlin; Lee, H., Kepley, L., Hong, H.-G., Mallouk, T., (1988) J. Am. Chem. Soc., 110, p. 618; Decher, G., Hong, J.-D., (1991) Ber. Bunsen-Ges., 95, p. 1430; Decher, G., (1997) Science, 227, p. 1232; Lvov, Y., Decher, G., Mohwald, H., (1993) Langmuir, 9, p. 481; Lvov, Y., Haas, H., Decher, G., Mohwald, H., Mikhailov, A., Mtchedlishvily, B., Morgunova, E., Vainshtein, B., (1994) Langmuir, 10, p. 4232; Kleinfeld, E., Ferguson, G., (1994) Science, 265, p. 370; Hong, J.-D., Lowack, K., Schmitt, J., Decher, G., (1993) Prog. Colloid Polym. Sci., 93, p. 98; Schmitt, J., Grunewald, T., Krajer, K., Pershan, P., Decher, G., Loshe, M., (1993) Macromolecules, 26, p. 7058; Korneev, D., Lvov, Y., Decher, G., Schmitt, J., Yarodaikin, S., (1995) Physica B, 214, p. 954; Iodine-125, a Guide to Radioiodination Techniques (1993), p. 64. , Amersham Life ScienceHwan, M.K., Sang, B.H., Moon, S.K., Jong, S.K., Goo, T.O., Dong, H.H., (1996) J. Pharmacol. Toxicol. Methods, 36, pp. 163-169; Adamson, A.W., Gast, A.P., (1997) Physical Chemsitry of Surfaces, pp. 27-28. , John Wiley & Sons: New York; Klagsbrum, M., (1979) Methods Enzymol., 58, p. 560; Blum, R.N., Wright, R.A., (1992) J. Gen. Intern. Med., 7, pp. 140-144; Okuda, M., Miura, I., Juji, F., Takashima, H., (1994) Int. Arch. Allergy Immunol., 104 (1 SUPPL. 1), pp. 6-8; Mosmann, T., (1983) J. Immunol. Methods, 65, pp. 55-63; Zund, G., Ye, Q., Hoerstrup, S.P., Schoeberlein, A., Schmid, A.C., Grunenfelder, J., Vogt, P., Turina, M., (1999) Eur. J. Cardio-thoracic Surg., 15, pp. 519-524; Risbud, M.V., Bhonde, M.R., Bhonde, R.R., (2001) J. Biomed. Mater. Res., 57, pp. 300-305; Strand, B.L., Ryan, T.L., In't Veld, P., Kulseng, B., Rokstad, A.M., Skjak-Brek, G., Espevik, T., (2001) Cell Transplant., 10, pp. 263-275; De Ceuninck, F., Gaufillier, S., Bonnaud, A., Sabatini, M., Lesur, C., Pastoureau, P., (2001) Biochem. Biophys. Res. Commun., 285, pp. 926-931; Bancel, S., Hu, W.S., (1996) Biotechnol. Prog., 12, pp. 398-402; Davids, S., (1993) Test Procedures for the Blood Compatibility of Biomaterials, pp. 287-330. , Kluwer Academic Publishers: Dordrecht
Keywords: animal cell; Animalia; Animals; article; Atomic force microscopy; biodegradability; biomaterial; cartilage cell; cell activity; cell adhesion; cell function; cell growth; cell proliferation; cell structure; Cells, Cultured; Chondrocytes; confocal laser microscopy; controlled study; Electron Probe Microanalysis; Electrostatics; extracellular matrix; Fourier transform infrared spectroscopy; gelatin; macromolecule; Macromolecules; Microscopy, Atomic Force; nonhuman; polyelectrolyte; Polyesters; Polyethyleneimine; Polyethylenes; polylactide; priority journal; protein analysis; protein stability; quantitative analysis; Rabbits; radioiodination; Scanning electron microscopy; Self assembly; Spectrophotometry, Ultraviolet; Spectroscopy, Fourier Transform Infrared; Surface charge; Surface engineering; Surface Properties; Tissue engineering; Ultraviolet spectroscopy; X ray photoelectron spectroscopy

Densification route and mechanical properties of Si 3N 4-bioglass biocomposites - Amaral, M.; Lopes, M.A.; Silva, R.F.; Santos, J.D. (BiomaterialsBiomaterials, 2002)
The processing route and the final microstructural and mechanical characteristics of a novel biomaterial composite are described. This new material is composed of 70 wt% Si 3N 4 ceramic phase and 30 wt% bioglass, the later performing as a liquid sintering aid system and simultaneously providing bioactivity characteristics to the composite. The conditions for fabrication of an almost fully dense material (∼98% of relative density) were pursued. Optimised parameters were 1350°C-40min-30 MPa by hot-pressing technique. The very fast densification rate of the process avoided the crystallisation of the bioglass intergranular phase and therefore its intrinsic properties were maintained. Also, the large amount of glassy phase assured the densification by liquid phase assisted grain rearrangement without Si 3N 4 phase transformation. The final mechanical properties of the Si 3N 4-bioglass were as follows: fracture toughness, K IC = 4.4 MPa m 1/2; Vickers hardness, H V = 10.3 GPa; Young's modulus, E = 197 GPa; bending strength, σ R = 383 MPa; Weibull modulus, m = 8.3. These values provide an attractive set of properties among other bioactive materials, namely by upgrading the main drawback of bioceramics and bioglasses for high-load medical applications, which is the lack of satisfactory fracture toughness. © 2001 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 33Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(01)00194-6PubMed ID: 11771704Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Secção de Materiais, Fac. Eng. da Univ. do Porto (FEUP), Universidade do Porto, Rua Roberto Frias, 4200-465 Porto Cedex, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Biocompatible Materials; Bioglass; Ceramics; Composite Resins; Silicon Compounds; silicon nitride, 12033-89-5Tradenames: BioglassReferences: Kue, R., Sohrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteacalcin production by human osteablast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201;Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clin Orthop, 244, pp. 296-301; Hench, L.L., Biomaterials: A forecast for the future (1998) Biomaterials, 19, pp. 1419-1423; Radin, S., Ducheyne, P., Falaize, S., Hammond, A., In vitro transformation of bioactive glass granules into Ca-P shells (2000) J Biomed Mater Res, 49, pp. 264-272; Santos, J.D., Amaral, M., Oliveira, S.M., Lopes, M.A., Silva, R.F., Silicon Nitride-Bioglass®45S5 composite for biomedical applications (2001) Key Eng Mater, 192-195, pp. 589-592; Gazzara, C.P., Messier, D.R., Determination of phase content of Si 3N 4 by X-ray diffraction analysis (1997) Am Ceram Soc Bull, 56 (9), pp. 777-780; Niihara, K., Morena, R., Hasselman, D.P., Evaluation of K IC of brittle solids by the indentation method with low crack-to-indent ratios (1982) J Mater Sci Lett, 1, pp. 13-16; Standard test method for dynamic Young's modulus, shear modulus, and Poisson's ratio for advanced ceramics by impulse excitation of vibration; Kingery, W.D., Densification during sintering in the presence of a liquid phase. I. Theory (1959) J Appl Phys, 30 (3), pp. 301-306; Ziegler, G., Heinrich, J., Wötting, G., Review: Relationships between processing, microstructure and properties of dense and reaction-bonded silicon nitride (1987) J Mater Sci, 22, pp. 3041-3086; Filho, O.P., LaTorre, G.P., Hench, L.L., Effect of crystallization on apatite-layer formation of bioactive glass 45S5 (1996) J Biomed Mater Res, 30, pp. 509-514; Evans, A.G., Wilshaw, T.R., Quasi-static solid particle damage in brittle solids I. Observations, analysis and implications (1976) Acta Metall, 24, pp. 939-956; Yamamuro, T., Reconstruction of the iliac crest with bioactive glass-ceramic prostheses (1990) Handbook of Bioactive Ceramics, 1, pp. 335-342. , Yamamuro T, Hench LL, Wilson J, editors. Boca Raton: CRC Press; Hench, L.L., Bioceramics (1998) J Am Ceram Soc, 81, pp. 1705-1728; Ravaglioli, A., Krajewski, A., (1992) Bioceramics - materials, properties and applications, , London: Chapman & Hall; Kong, Y.M., Kim, S., Kim, H.E., Reinforcement of hydroxyapatite bioceramic by addition of ZrO 2 coated with Al 2O 3 (1999) J Am Ceram Soc, 82 (11), pp. 963-968; Ducheyne, P., Marcolongo, M., Schepers, E., Bioceramic composites (1993) An Introduction to Bioceramics. Advanced series in ceramics, 1, pp. 281-297. , Hench L, Wilson J, editors. Singapore: World Scientific. Chapter 15
Keywords: 3N; 4-bioglass composites; article; Bending strength; Biocompatible Materials; biomaterial; Biomaterial composites; Biomaterials; Ceramic materials; ceramics; Composite Resins; Crystallization; Densification; Densification behaviour; density; Elastic moduli; Fracture toughness; glass; hardness; heat; Hot pressing; Hot-pressing; Kinetics; Mechanical properties; phase transition; Phase transitions; priority journal; Si; Silicon compounds; silicon derivative; Sintering; strength; Stress, Mechanical; technique; Thermodynamics; Vickers hardness testing; X-Ray Diffraction; young modulus

Electrochemical and microstructural studies of tantalum and its oxide films for biomedical applications in endovascular surgery - Silva, R.A.; Walls, M.; Rondot, B.; Da Cunha Belo, M.; Guidoin, R. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2002)
The most popular coronary stents are made of 316L stainless steel and self-expandable Nitinol. Nevertheless, Ta has already been used to make stents for endovascular surgery and may constitute a good alternative to the other materials because of its higher corrosion resistance and radio-opacity property, which may facilitate the follow-up of stent catheterization. The characterization of Ta and its natural passive oxide films has been performed in a 0.15M NaCl solution (simulated body fluid - SBF) using anodic polarizations, electrochemical impedance spectroscopy and photoelectrochemical techniques. Changes in microstructure have been observed by atomic force microscopy (AFM). Polarization curves show the existence of a current density increase between 1.40 and 1.80V. Bode complex plots show that some perturbation of the film occurred in this potential interval which may be associated with a decrease in polarization resistance, Rp, indicating that the film may be less resistant to corrosive attack. Mott-Schottky capacity measurements show that the density of donors, Nd, varies with polarization. The optical band gap, E g, which is equal to 4.1 eV did not show variations in our experiments. The localized formation on the electrode surface, in the above potential interval of a Ta compound (possibly an oxide-hydroxide) was observed by AFM, and this may explain the appearance of the current density peak and capacity behavior at those potentials. © 2002 Kluwer Academic Publishers.
Cited By (since 1996): 17Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1014779008598Language of Original Document: EnglishCorrespondence Address: Silva, R.A.; CIEA/ISEP, Rua S. Tomé, 4200 Porto, PortugalReferences: Sigwart, U., Puel, J., Mirkovitch, V., Joffre, F., Kappenberger, L., (1987) New Engl. J. Med., 316 (12), pp. 701-706;Serruys, P.W., De Jaegere, P., Kiemeneij, F., Macaya, C., Heindrickx, W., (1994) New Engl. J. Med., 331 (8), pp. 489-495; Fischman, D.L., Leon, M.B., Baim, D.S., Schatz, R.A., Savage, M.P., Penn, I., (1994) New Engl. J. Med., 331 (8), pp. 496-501; Serruys, P.W., Emanuelsson, H., Van Der Giessen, W., Lunn, A.C., Kiemeney, F., Macaya, C., (1996) Circulation, 93 (3), pp. 412-422; Cohen, D.J., Breall, J.A., Ho, K.K., Kuntz, R.E., Goldman, L., Baim, D.S., (1995) New Engl. J. Med., 92, pp. 1859-1874; Cohen, D.J., Breall, J.A., Ho, K.K., Weintraub, R.M., Kuntz, R.E., Weistein, M.C., (1993) J. Amer. Coll. Cardiology, 22 (4), pp. 1052-1059; Cohen, D.J., Krumholz, H.M., Sukin, C.A., Ho, K.K., Siegrist, R.B., Cleman, M., (1995) Circulation, 92, pp. 2480-2487; Colombo, A., Hall, P., Nakamura, S., Almagor, Y., Maiello, L., Martini, O., (1995) Circulation, 91 (6), pp. 1676-1688; Goy, J.J., Eeckhout, E., Stauffer, J.C., Vogt, P., Kappenberger, L., (1995) Catheter. Cardiov. Diag., 34, pp. 128-132; Hamasaki, N., Nosaka, H., Nobuyoshi, M., (1995) J. Amer. Coll. Cardiol., 239 A (SPEC. ISSUE); Hamm, C.W., Beythien, C., Sievert, H., Langer, A., (1995) Amer. Heart J., 129 (3), pp. 423-429; Kiemeneij, F., Hofland, J., Laarman, G.J., Hupkens Van der Elst, D., Van der Lubbe, H., (1995) Catheter. Cardiov. Diag., 35, pp. 301-308; Mehan, V.K., Kaufmann, U., Urban, P., Chatelain, P., Meier, B., (1995) Catheter. Cardiov. Diag., 34, pp. 122-127; Robinson, N.M., Thomas, M.R., Jewitt, D.E., Wainwright, R.J., (1995) Cardiology, 7 (6), pp. 156-164; Stauffer, J.C., Eeckhout, E., Goy, J.J., Nacht, C.A., Vogt, P., Kappenberger, C., (1995) J. Invas. Cardiol., 7 (8), pp. 221-227; Webb, J., Stertzer, S., Ahmad, T., Carere, R., Mercier, B., Dodek, A., (1996) Catheter. Cardiov. Diag., 37, pp. 120-124; Schöneberger, A.A., Schmidt, K., (1996) New Engl. J. Med., 335 (15), p. 1160; Priestley, K.A., Clague, J.R., Buller, N.P., Sigwart, U., (1996) Europ. Heart J., 17 (3), pp. 438-444; Silva, R.A., Marques, M.A., Silveira, A., Walls, M., Rondot, B., Guidoin, R., (1998) Proceedings of the 14th European Conference on Biomaterials, p. 37. , The Hague, September, edited by the Dutch Society for Biomaterials; Pypen, C.M.J.M., Plenk H., Jr., Ebel, M.F., Svagera, R., Verenisch, J., (1997) J. Mater. Sci. Mater. Med., 8, pp. 781-784; Park, J.B., (1984) Biomaterials Science and Engineering, p. 217. , New York, Plenum Press; Jonhson, P.F., Bernstein, J.J., Hunter, G., Dawson, W.W., Hench, L.L., (1977) J. Biomed. Mater. Res., 11, pp. 637-656; Black, J., (1994) Clin. Mater., 16, pp. 167-173; Stackpool, G.J., Kay, A.B., Morton, P., Harvey, E.J., Tanzer, M., Bone, J.D., (1995) Proceedings of Combined Orthopaedic Research Societies Meeting, p. 45. , edited by Orthopaedic Research Society (Rider Dickerson Inc., Chicago); Macagno, V.A., Schultze, J.W., (1984) J. Electroanal. Chem., 180, pp. 157-170; Schultze, J.W., Macagno, V.A., (1986) Electrochim. Acta, 31, pp. 355-363; Kerrec, O., Devilliers, D., Groult, H., Chemla, M., (1995) Electrochim. Acta, 40, pp. 719-724; Degryse, R., Gomes, W.P., Cardon, F., Vennik, J., (1975) J. Electrochem. Soc., 122, p. 711; Gartner, W.W., (1959) Phys. Rev., 116, p. 84; Butler, M.A., (1977) J. Appl. Phys., 48, p. 1914; Ginley, D.S., Butler, M.A., (1977) J. Appl. Phys., 48, p. 2019; Clechet, P., Martin, J.-R., Olier, R., Vallouy, C., (1976) C. R. Acad. Sci. Paris, 282, pp. 887-890; Lohrengel, M.M., (1994) Electrochim. Acta, 39, pp. 1265-1271
Keywords: article; Atomic force microscopy; body fluid; coronary stent; Corrosion; Corrosion resistance; Current density; Electric Potential; electrochemical analysis; Electrochemical impedance spectroscopy; electrochemistry; electrode; endovascular surgery; Energy gap; film; heart catheterization; hydroxide; Materials science; metal oxide; Metallic films; Microstructure; nitinol; optical density; Oxide films; Polarization; priority journal; simulation; sodium chloride; Stainless steel; structure analysis; Surgery; Tantalum; Tantalum compounds; tantalum oxide; unclassified drug

Mathematical model for educational simulation of the oxygen delivery to the fetus - Sá Couto, P.M.; van Meurs, W.L.; Bernardes, J.F.; Marques De Sá, J.P.; Goodwin, J.A. (Control Engineering PracticeControl Eng. Pract., 2002)
Critical situations in obstetrics and anesthesia of the pregnant woman are rare and associated with a high risk to the woman and fetus involved. Therefore, simulation is a valuable tool in teaching the diagnostic and therapeutic skills in this context. We derive a mathematical model for the oxygen supply to the fetus that was specifically designed for educational simulations. The model reflects the hemodynamics and the oxygen transport. Parameter values for human patients are derived from the literature data. We validate the response of the model, with parameters reflecting the fetal lamb, to various reductions of the uterine and umbilical blood flow. © 2002 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: COEPEdoi: 10.1016/S0967-0661(01)00133-2Language of Original Document: EnglishCorrespondence Address: Marques de Sá, J.P.; Instituto de Engenharia Biomedica, Faculdade de Engenharia, Universidade do Porto, Rua Roberto Frias, Porto 4200-465, Portugal; email: jmsa@fe.up.ptReferences: Beneken, J.E.W., Rideout, V.C., The use of multiple models in cardiovascular system studies: Transport and perturbation methods (1968) IEEE Transactions on Bio-Medical Engineering, 15 (4), pp. 281-289;Cunningham, G., (1997) Williams Obstretrics, , (20th ed.). London: Prentice-Hall; Delivoria-Papadopoulos, M., McGowan, J.E., Oxygen transport and delivery (1998) Fetal and Neonatal Physiology, pp. 1105-1117. , R. A. Polin and W. W. Fox (Eds.), (2nd ed.) London: W.B. Saunders Company; Euliano, T.Y., Caton, D., van Meurs, W.L., Good, M.L., Modeling obstetric cardiovascular physiology on a full-scale patient simulator (1997) Journal Clinical Monitoring, 13 (5), pp. 293-297; Fukui, Y., Smith, N.T., Interactions among ventilation, the circulation, and the uptake and distribution of halothane-use of a hybrid computer multiple model: I the basic model (1981) Anesthesiology, 54, pp. 107-118; Fukui, Y., Smith, N.T., Interactions among ventilation, the circulation, and the uptake and distribution of halothane-use of a hybrid computer multiple model: II spontaneous vs. controlled ventilation, and the effects of CO 2 (1981) Anesthesiology, 54, pp. 119-124; Gaba, D.M., De Anda, A., A comprehensive anesthesia simulation environment: Recreating the operating room for research and training (1988) Anesthesiology, 69, pp. 387-394; Good, M.L., Gravenstein, J.S., Anesthesia simulators and training devices (1989) International Anesthesiololy Clinics, 27 (3), pp. 161-168; Guyton, A.C., (1991) Medical Physiolology, , (8th ed.). London: W.B. Saunders Company; Henson, L., Lee, A., (1998) Simulators in Anesthesiology Education, , New York: Plenum; Huikeshoven, F.J., Hope, I.D., Power, G.G., Gilbert, R.D., Longo, L.D., Mathematical model of fetal circulation and oxygen delivery (1985) American Journal of Physiology, 249, pp. R192-R202; Itskovitz, J., LaGamma, E., Rudolph, A.M., The effect of reducing umbilical blood flow on fetal oxygenation (1983) American Journal of Obstetric and Gynecology, 145 (7), pp. 813-818; Polin, R.A., Fox, W.W., (1998) Fetal and Neonatal Physiology, , (2nd ed.). London: W.B. Saunders Company; Schwid, H.A., Flight simulator for general anesthesia training (1987) Computers and Biomedical Research, 20, pp. 64-75; Schwid, H.A., O'Donnell, D., The anesthesia simulator- recorder: A device to train and evaluate anesthesiologists' responses to critical incidents (1990) Anesthesiology, 72, pp. 191-197; Severinghaus, J.W., Simple, accurate equations for human blood O 2 dissociation computations (1979) Journal of Applied Physiology, 46 (3), pp. 599-602; Skillman, C.A., Plemessinger, M.A., Woods, J.R., Clark, K.E., The effect of graded reductions in uteroplacental blood flow on fetal lamb (1985) American Journal of Physiology, 249 (18), pp. H1098-H1105; Sukumar, N., Morin III, F.C., Response of the fetal circulation to stress (1998) Fetal and Neonatal Physiology, pp. 1014-1023. , (2nd ed.) London: WB Saunders Company; van Meurs, W.L., Good, M., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) Journal of Clinical Monitoring, 13 (5), pp. 317-324; Zwart, A., Smith, N.T., Beneken, J.E.W., Multiple model approach to uptake and distribution of halothane: The use of an analog computer (1972) Computers and Biomedical Research, 5, pp. 228-238
Keywords: Anesthesiology; Blood; Computer simulation; control; Diagnosis; education; Fetal monitoring; fetus; hemodynamics; mathematical model; Mathematical models; medical application; Obstetrics; oxygen; Oxygen supply; simulator; Therapeutic skills

A novel urethane containing copolymer as a surface modification additive for blood contact materials - Ji, J.; Barbosa, M.A.; Feng, L.; Shen, J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2002)
Surface modification to develop a biomolecules-presenting surface is of interest, both from a scientific and an industrial point of view. In this research, a penta-block-coupling polymer of warfarin-PEO-MDI-PEO-warfarin was specially designed as the surface modifying additive (SMA). The warfarin-modified polyurethane surfaces were then prepared by dip-coating method. Attenuated total reflection fourier transform infra-red (ATR-FTIR) spectra revealed that the urethane segments in the SMA could penetrate into the hard block of segmented polyurethane (SPU) via intermolecular hydrogen bonds. The X-ray photoelectron spectroscopy (XPS) results indicated that the intermolecular hydrogen bonds were strong enough to form stable warfarin-PEO composite surfaces in an aqueous environment. Fibrinogen and albumin adsorption onto unmodified and SMA-modified SPU was investigated by the 125l-labeled method. The surface for attracting and reversibly binding albumin, which was proved to suppress the platelet adhesion and prolong the clotting time, has been developed by the simple coating of the novel SMA in SPU. © 2002 Kluwer Academic Publishers.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1015789726455Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, HangZhou 310027, China; email: jianji@mail.hz.zj.cnReferences: Elbert, D., Hubbell, J., (1996) Annu. Rev. Mater., p. 365;Munro, M., Quattrone, A., Ellsworth, S., Kulkarni, P., Eberhart, R., (1981) Trans. Am. Soc. Artif. Intern. Organs., p. 499; Park, K., Okano, T., Nojiri, C., Kim, S., (1988) J. Biomed. Mater. Res., p. 977; Han, D., Jeong, S., Kim, Y., Min, B., Cho, H., (1991) J. Biomed. Mater. Res., p. 561; Ji, J., Feng, L.X., Barbosa, M.A., (2001) Biomaterials, 22, p. 3015; Ji, J., Feng, L.X., Qiu, Y.X., Yu, X.J., Barbosa, M.A., (2000) J. Colloid Interfac. Sci., 15, p. 224; (2000) J. Colloid Interfac. Sci., 15, pp. 255-260; Ji, J., Feng, L.X., Qiu, Y., Yu, X., (2000) Polymer, p. 3713; Ishihara, K., Hanyuda, H., Nakabayashi, N., (1995) Biomaterials, p. 873; Amiji, M., Park, K., (1993) J. Biomater. Sci. Polym. Ed., p. 217; Lamba, N., Woodhouse, K., Cooper, S.L., (1998) Polyurethanes in Biomedical Applications, p. 43. , CRC Press, New York; Nelson, K.D., Eisenbaumer, R., Pomerantz, M., Eberhart, R.C., (1996) ASAIO Journal, p. 884; Wang, D.A., Ji, J., Feng, L.X., (2000) Macromol. Chem. Phys., p. 1574; Wang, D.A., Ji, J., Feng, L.X., (2000) Macromolecules, p. 8472; Brash, J.L., Davidson, V.J., (1976) Thromb. Res., p. 249; Qiu, Y.X., Yu, X.J., Feng, L.X., (1992) Markromol. Chem., p. 1377; Okkema, A.Z., Grasel, T.G., Zdrahala, R.J., Solomon, D.D., Cooper, S.L., (1989) J. Biomater. Sci. Polym. Ed., p. 43; Takahara, A., Jujo, A.N., Kajiyama, N.T., (1989) J. Biomater. Sci. Polym. Ed., p. 17
Keywords: Adhesion; Adsorption; Albumin; article; Attenuation; biomaterial; Block copolymers; Blood; blood clotting time; Chemical modification; Coatings; copolymer; fibrinogen; Fourier transform infrared spectroscopy; human; human cell; hydrogen bond; Hydrogen bonds; infrared spectroscopy; iodine 125; material coating; Polyurethanes; priority journal; Surface modifying additives (SMA); surface property; Surface treatment; synthesis; thrombocyte adhesion; urethan; warfarin; X ray photoelectron spectroscopy

Porous glass reinforced hydroxyapatite materials produced with different organic additives - Prado da Silva, M.H.; Lemos, A.F.; Gibson, I.R.; Ferreira, J.M.F.; Santos, J.D. (Journal of Non-Crystalline SolidsJ Non Cryst Solids, 2002)
In the present study three different organic additives were used to produce porous structures of a CaO-P 2O 5 glass reinforced hydroxyapatite potato starch, almond crust and wax spheres. The produced samples were analysed by scanning electron microscopy, X-ray diffraction with Rietveld refinement, differential thermal analysis and mercury porosimetry. The techniques used in this study enabled the production of glass reinforced hydroxyapatite samples with various pore diameters. Two different techniques were used to produce porous glass reinforced hydroxyapatite samples: a dry method using wax spheres as pore formers and a wet method in alcoholic suspension, where almond crust and potato starch were used as pore formers. The final microstructure consists of hydroxyapatite, α-tricalcium phosphate and β-tricalcium phosphate. X-ray diffraction and scanning electron microscopy analysis revealed different percentages of phases when comparing dense and porous glass reinforced hydroxyapatite specimens. These hard materials are intended to be used as bone defect fillers. © 2002 Elsevier Science B.V. All rights reserved.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: JNCSBdoi: 10.1016/S0022-3093(02)01036-0Language of Original Document: EnglishCorrespondence Address: Prado da Silva, M.H.; DEM, Universidade Federal do Ceara, PO Box 12144, 60455-760 Fortaleza, CE, Brazil; email: mpsilva@ibmc.up.ptReferences: Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., (2000) Biomaterials, 21, p. 813;Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 47, p. 603; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 45, p. 376; Silva, P.L., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) Surf. Coat. Tech., 102, p. 191; Zhang, Y., Santos, J.D., (2000) J. Non-Cryst. Solids, 272, p. 14; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., (1995) J. Mater. Sci: Mat. Med., 6, p. 348; Santos, J.D., Jha, L.J., Monteiro, F.J., (1996) J. Mater. Sci: Mater. Med., 7, p. 181; Lemos, A.F., Ferreira, J.M.F., (2000) Mater. Sci. Eng, 11, p. 35; Lyckfeldt, O., Ferreira, J.M.F., (1998) J. Eur. Ceram. Soc., 18, p. 131; Saggio-Woyansky, J., Scott, C.E., Minnear, W.P., (1992) Am. Ceram. Soc. Bull., 71, p. 1674; De Groot, K., Klein, C.P.A.T., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., (1990) Hand. Bioact. Cer., 2, p. 3. , CRC, Boca Raton, FL; Knowles, J.C., Santos, J.D., Hastings, G.W., patent number WO0068164, 2000Larson, A.C., Von Dreele, R.B., Lujan M., Jr., GSAS, Neutron Scattering Centre, Los Alamos National Laboratory, CA, 1990Kay, M.I., Young, R.A., Posner, A.S., (1964) Nature, 204, p. 1050; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244
Keywords: Additives; Differential thermal analysis; Fillers; glass; hydroxyapatite; Microstructure; Porosimeters; Porous glasses; Porous materials; Scanning electron microscopy; Suspensions (fluids); X ray diffraction analysis

Preparation of albumin preferential surfaces on poly(vinyl chloride) membranes via surface self-segregation - Ji, A.; Feng, L.; Shen, J.; Barbosa, M.A. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 2002)
Poly(vinyl chlorides)-graft-[w-stearyl-poly(ethylene oxide)] (PVC-g-SPEO), which has a poly(vinyl chloride) (PVC) backbone, poly(ethylene oxide) (PEO) side chain, and stearyl end groups, has been synthesized. Self-organizing blends of the amphiphilic comb polymer in poly-(vinyl chlorides) have been examined as a means to create albumin preferential surfaces on polymer films. X-ray photoelectron spectroscopy (XPS) analysis indicates substantial surface segregation of the PVC-g-SPEO. A surface concentration of 59.9 EO wt % is achieved by the solution casting and heat treatment of a film with a bulk concentration of only 3.78 EO wt %. In the aqueous environment, the surface rearrangement of PVC-g-SPEO/PVC blend film is limited and presents a high interfacial energy and high depolar component of interfacial energy due to the "tail-like" SPEO side chain. Protein adsorption tests confirm that PVC-g-SPEO/PVC blend films absorb high levels of albumin and dramatically resist fibrinogen adsorption. Surfaces to attract and reversibly bind albumin, which might diminish the occurrence of thrombosis, inflammation, and infection, are developed by self-organizing blends of the amphiphilic comb polymer in poly(vinyl chlorides). © 2002 Wiley Periodicals, Inc.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/jbm.10187Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, HangZhou, 310027, China; email: jianji@mail.hz.zj.cnChemicals/CAS: Membranes, Artificial; Polyethylene Glycols; Polyvinyl Chloride, 9002-86-2; Serum Albumin; Stearates; stearyl poly(ethylene oxide)References: Blass, C.R., Jones, C., Courtney, J.M., Biomaterials for blood tubing: The application of plasticised poly(vinyl chloride) (1992) Int J Artif Organs, 15 (4), pp. 200-203;Brash, J.L., (1983) Biocompatible polymer, metals and composites, p. 35. , Szycher M, editor. London, UK: Technomic Pub. Co; Keogh, J.R., Velander, F.F., Eaton, W., Albumin-binding surfaces for implantable devices (1992) J Biomed Mater Res, 26 (4), pp. 441-456; Amiji, M., Park, K., Surface modification of polymeric biomaterials with poly(ethylene oxide), albumin, and heparin for reduced thrombogenicity (1993) J Biomater Sci Polym Ed, 4 (3), pp. 217-234; Ji, J., Feng, L., Barbosa, M.A., Stearyl poly(ethylene oxide) grafted surfaces as albumin preferential materials (2001) Biomaterials, 22, p. 3015; De Queiroz, A.A., Barrak, E.R., Gil, H.A., Higa, O.Z., Surface studies of albumin immobilized onto PE and PVC films (1997) J Biomater Sci Polym Ed, 8 (9), pp. 667-681; McFarland, C.D., Jenkins, M., Griesser, H.J., Chatelier, R.C., Steele, J.G., Underwood, P.A., Albumin-binding surfaces: Synthesis and characterization (1998) J Biomater Sci Polym Ed, 9 (11), pp. 1207-1225; Wang, D.A., Ji, J., Sun, Y.H., Yu, G.H., Feng, L.X., Blends of stearyl poly(ethylene oxide) coupling-polymer in chitosan as coating materials for polyurethane intravascular catheters (2001) J Biomed Mater Res, 58 (4), pp. 372-383; Wang, D.A., Ji, J., Gao, C.Y., Yu, G.H., Feng, L.X., Surface coating of stearyl poly(ethylene oxide) coupling-polymer on polyurethane guiding catheters with poly(ether urethane) film-building additive for biomedical applications (2001) Biomaterials, 22 (12), pp. 1549-1562; Ji, J., Feng, L., Qiu, Y., Yu, X., Barbosa, M.A., Self-assembly and surface structure of an amphiphilic graft copolymer, polystyrene-graft-omega-stearyl-poly(ethylene oxide) (2000) J Colloid Interface Sci, 224 (2), pp. 255-260; Jian, J., Feng, L., Qiu, Y., Yu, X., Stearyl poly(ethylene oxide) grafted surfaces for preferential adsorption of albumin Part 2 (2000) The effect of molecular mobility on protein adsorption Polymer, 41 (10), pp. 3713-3718; Wu, S., (1982) Polymer Interface and adhesion, , New York: Marcel Dekker; Garbassi, F., Morra, M., Occhliello, E., (1994) Polymer surface: From physics to technology, , New York: John Wiley & Sons; Walton, D.G., Mayes, A.M., Entropically-driven segregation in blend of branch and linear polymers (1996) Phys Rev E, 54 (3), pp. 2811-2815; Mayes, A.M., Irvine, D.J., Griffith, L.G., Tailoring polymer surfaces for control cell behavior (1998) Biomaterials regulating cell function and tissue development, pp. 73-86. , Thomson RC, Mooney DJ, Healy KE, Ikada T, Mikos AG, editors. Warrendale: Materials Research Society; Eberhart, R.C., Munro, M.S., Williams, G.B., Kulkarni, P.V., Shannon W.A., Jr., Brink, B.E., Fry, W.J., Albumin adsorption and retention on C18-alkyl-derivatized polyurethane vascular grafts (1987) Artif Organs, 11 (5), pp. 375-382; Grasel, T.G., Pierce, J.A., Cooper, S.L., Effects of alkyl grafting on surface properties and blood compatibility of polyurethane block copolymers (1987) J Biomed Mater Res, 21 (7), pp. 815-842; Gombotz, W.R., Guanghui, W., Horbett, T.A., Hoffman, A.S., Protein adsorption to poly(ethylene oxide) surfaces (1991) J Biomed Mater Res, 25 (12), pp. 1547-1562; Neumann, A.W., Goog, R.J., Surface and colloid science, experimental methods (1979), 11, p. 31. , New York: Plenum PressAndrade, J.D., Ma, S.M., Contact angle at the S-W interface (1979) J Colloid Interface Sci, 72, pp. 488-494; Brash, J.L., Davidson, V.J., Adsorption of glass and polyethylene from solutions of fibrinogen and albumin (1976) Thromb Res, 9 (3), pp. 249-259; Ranter, B.D., (1985) Surface and interfacial aspects of biomedical polymers, p. 374. , Andrade JD, editor. New York: Plenum Press; Van Oss, C.J., (1994) Interfacial forces in aqueous media, pp. 170-177. , Van Oss CJ, editor. New York: Marcel Dekker; Wu, D., Jian, K., (1995) Sci China (B), 25 (11), p. 1121; Wu, D., (1995) Jian K Sci China (B), 26 (5), p. 409; Jeon, S.I., Lee, J.H., Andrade, J.D., De Gennes, P.G., Protein-surface interactions in the presence of polyethylene oxide (1991) J Coll Interface Sci, 142 (1), pp. 149-158; Hester, J.F., Banerjee, P., Mayes, A.M., Preparation of protein-resistant surfaces on poly(vinylidene fluoride) membranes via surface segregation (1999) Macromolecules, 32 (5), pp. 1643-1650; Keogh, R.J., Eaton, J.W., Albumin binding surfaces for biomaterials (1994) J Lab Clin Med, 124 (4), pp. 537-545
Keywords: Adsorption; Albumin; Amphiphilic copolymer; amphophile; aqueous solution; article; artificial membrane; Biocompatible Materials; cell separation; cell surface; chemical binding; combinatorial chemistry; concentration response; conference paper; dimerization; energy resource; film; human; Humans; infection; Inflammation; Inflammations; macrogol; macrogol derivative; membrane structure; Membranes, Artificial; metabolism; Plastic films; Polyethylene Glycols; polymer; Polymeric membranes; Polyvinyl Chloride; Polyvinyl chlorides; polyvinylchloride; protein binding; Serum Albumin; Stearates; stearic acid derivative; stearyl poly(ethylene oxide); Surface modification; Surface Properties; surface property; Surface segregation; Synthesis (chemical); thrombosis; X ray analysis; X ray photoelectron spectroscopy

Production of porous biomaterials based on glass-reinforced hydroxyapatite composites - Prado da Silva, M.H.; Lemos, A.F.; Ferreira, J.M.F.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2002)
In this study, porous GR-HA composites were produced using a calcium-phosphate glass with the composition, in mol%, 75P 2O 5-15CaO-10CaF 2. The composites were obtained by wet mixing 4.0% (w/w) of the glasses with hydroxyapatite (HA) powder (batch P120) (Plasma Biotal; Tideswell, U.K.), pressing and sintering. Two different organic additives were used as pore formers: potato starch and almond crust. This processing route was effective in producing a homogeneous microstructure of equiaxed grains. The bulk density of the samples decreased with the volume fraction increase in the content of pore formers. Scanning electron microscopy and mercury porosimetry analyses showed to be complementary techniques in characterising the pore size and distribution.
Conference code: 60281Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Prado da Silva, M.H.; Instituto de Engenharia Biomedica, Laboratório de Biomaterials, Rua do Campo Alegre 823, PT-4150-180 Porto, PortugalReferences: Lemos, A.F., Ferreira, J.M.F., (2000) Materials Science and Engineering, 11, pp. 35-40;Saggio-Woyansky, J., Scott, C.E., Minnear, W.P., (1992) Amer. Cer. Society Bulletin, 71 (11), pp. 1674-1682; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inouue, H., (2001) J. Biom. Mater. Res., 54, pp. 463-469; Knowles, J.C., Santos, J.D., Hastings, G.W., (2000) Sintered Hydroxyapatite Composition and Method for the Preparation thereof, , Patent number WO0068164
Keywords: Biomaterials; Composite materials; glass; Glass-reinforced hydroxyapatite composites; GR-HA Composites; hydroxyapatite; Macroporous Bioceramics; Mercury (metal); Microstructure; Organic Additives; Pore size; Porous materials; Powders; Pressing (forming); Scanning electron microscopy; Sintering; Starch

Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and support the osteogenic differentiation of human bone marrow cells - Amaral, M.; Costa, M.A.; Lopes, M.A.; Silva, R.F.; Santos, J.D.; Fernandes, M.H. (BiomaterialsBiomaterials, 2002)
The in vitro osteocompatibility of a novel Si 3N 4-bioglass composite (70-30% weight proportion) with improved mechanical properties (fracture toughness=4.4MPam 1/2; bending strength=383±47MPa) is reported. Immersion of the composite samples in culture medium (30min to 7 days) resulted in rapid protein adsorption to the surface and, also, dissolution of the intergranular phase of bioglass (time-dependent process) with the formation of different size cavities. "As-received" and pre-treated material samples presented a similar behaviour concerning the proliferation of MG63 osteoblast-like cells, evaluated during a 5-day culture period. Seeded materials showed a higher cell growth rate as compared to cultures performed on the standard plastic culture plates. To assess the osteogenic potential of the composite, "as-received" material samples were seeded with human bone marrow cells and cultured for 35 days in experimental conditions that favour the development of the osteoblastic phenotype. The cell adhesion process was similar to that observed in control cultures. Cells successfully adapted to the irregularities of the surface and were able to grow towards inside the cavities; in addition, osteogenic differentiation occurred with the formation of abundant cell-mediated mineralised deposits. Results suggest that this Si 3N 4-bioglass composite seems to be a promising candidate for high-stress medical applications. © 2002 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(02)00249-1PubMed ID: 12361631Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Universidade do Porto, Rua Dr Manuel Pereira da Silva, 4200-393 Porto, Portugal; email: mhrf@portugalmail.ptChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Calcium, 7440-70-2; Phosphorus, 7723-14-0; Silicon Compounds; silicon nitride, 12033-89-5References: Amaral, M., Lopes, M.A., Silva, R.F., Santos, J.D., Densification route and mechanical properties of Si 3N 4-bioglass biocomposites (2002) Biomaterials, 23, pp. 857-862;Kue, R., Sahrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201; Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clin Orthop, 244, pp. 296-301; Hench, L.L., Biomaterials: A forecast for the future (1998) Biomaterials, 19, pp. 1419-1423; Radin, S., Ducheyne, P., Falaize, S., Hammond, A., In vitro transformation of bioactive glass granules into Ca-P shells (2000) J Biomed Mater Res, 49, pp. 264-272; Santos, J.D., Amaral, M., Oliveira, S.M., Lopes, M.A., Silva, R.F., Silicon Nitride - Bioglass ® 45S5 composite for biomedical applications (2001) Key Eng Mater, 192-195, pp. 589-592; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Maniatopoulos, C., Sodek, J., Melcher, A., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblastic phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 43, pp. 213-221; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Stein, G.S., Lian, J.B., Stein, J.L., Van Wijnem, A.J., Frenkel, B., Montecino, M., Mechanisms regulating osteoblast proliferation and differentiation (1996) Principles of bone biology, pp. 69-86. , J.P. Bilizikian, L.G. Raisz, & G.A. Rodan. New York: Academic Press; Fernandes, M.H., Costa, M.A., Carvalho, G.S., Mineralization in serially passaged human alveolar bone cells (1997) J Mater Sci: Mater Med, 8, pp. 61-65; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II: Effect of ascorbic acid β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Costa, M.A., Fernandes, M.H., Long-term effects of parathyroid hormone, 1,25-dihydroxyvitamin D3 and dexamethasone on the cell growth and functional activity of human osteogenic alveolar bone cell cultures (2000) Pharmacol Res, 42, pp. 345-353; Coelho, M.J., Trigo Cabral, A., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part I: Osteoblastic differentiation of serially passaged human bone marrow cells cultured in α-MEM and in DMEM (2000) Biomaterials, 21, pp. 1087-1094; Aubin, J.E., Liu, F., The osteoblastic lineage (1996) Principles of bone biology, pp. 51-67. , J.P. Bilizikian, L.G. Raisz, & G.A. Rodan. New York: Academic Press; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P 2O 5 glass hydroxyapatite double layer plasma sprayed coatings: In vitro bioactivity evatuation (1999) J Biomed Mater Res, 45, pp. 376-383; Kokubo, T., Ito, S., Huang, Z.T., Hayashi, T., Sakka, S., Ca, P-rich layer formed on high-strenght bioactive glass-ceramic A-W (1990) J Biomed Mater Res, 24, pp. 331-343; Daculsi, G., Legeros, R.Z., Heughebaert, M., Barbieux, I., Formation of carbonato-apatite crystals after implantation of calcium phosphate ceramics (1990) Calcif Tissue Int, 46 (1), pp. 20-27; Neo, M., Nakamura, T., Ohtsuki, C., Kokubo, T., Yamamuro, T., Apatite formation on three kinds of bioactive material at an early stage in vivo: A comparative study by transmission electron microscopy (1993) J Biomed Mater Res, 27, pp. 999-1006; Bagambisa, F.B., Joos, U., Schilli, W., Mechanisms and structure of the bond between bone and hydroxyapatite ceramics (1993) J Biomed Mater Res, 27, pp. 1047-1055; Bagambisa, F.B., Kappert, H.F., Schilli, W., Interfacial reactions of osteoblast to dental and implant materials (1994) J Oral Maxillofac Surg, 52, pp. 52-56; De Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., Initial bone matrix formation at the hydroxyapatite interface (1995) J Biomed Mater Res, 29 (1), pp. 89-99; Hulshott, J.E.G., Van Kijk, K., De Ruijter, J.E., Rietveld, F.J.R., Ginsel, L.A., Jansen, J.A., Interfacial phenomena: An in vitro study of the effect of calcium phosphate (Ca-P) ceramic on bone formation (1998) J Biomed Mater Res, 40, pp. 464-474; De Santis, D., Guerriero, C., Nocini, P.F., Vangersbock, A., Richard, G., Gotte, P., Armato, U., Adult human bone cells from jaw bones cultured on plasma-sprayed or polished surfaces of titanium or hydroxyapatite discs (1996) J Mater Sci Mater Med, 7, pp. 21-28; Anselme, K., Sharrock, P., Hardouin, P., Dard, M., In vitro growth of human adult bone-derived cells on hydroxyapatite plasma-sprayed coatings (1997) J Biomed Mater Res, 34, pp. 247-259; Ferraz, M.P., Fernandes, M.H., Trigo Cabral, A., Santos, J.D., Monteiro, F.J., In vitro growth and differentiation of osteoblastic-like human bone marrow cells on a glass reinforced hydroxyapatite plasma-speayed coating (1999) J Mater Sci: Mater Med, 10, pp. 567-576; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of pre-immersion on the biocompatibility of glass-reinforced hydroxyapatite plasma sprayed coatings (2000) Biomaterials, 21, pp. 813-820; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., HA and double-layer HA/CaO-P 2O 5 glass coatings: Influence of chemical composition on human bone marrow cells osteoblastic behaviour (2001) J Mater Sci: Mater Med, 7, pp. 628-638; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Direct and indirect effects of P 2O 5-glass reinforced hydroxyapatite composites on the growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Gwynn, I.A.P., Cell biology at interfaces (1994) J Mater Sci Mater Med, 5, pp. 357-360; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681; KirkPatrick, C.J., Wagner, M., Kohler, H., Bittinger, F., Otto, M., Klein, C.L., The cell and molecular biological approach to biomaterial research: A perspective (1997) J Mater Sci Mater Med, 8, pp. 131-141; Verrier, S., Bareille, R., Rovira, A., Dard, M., Amedee, J., Human osteoprogenitor responses to orthopaedic implant: Mechanism of cell attachment and cell adhesion (1996) J Mater Sci Mater Med, 7, pp. 46-51; Dee, K.C., Rueger, D.C., Andersen, T.T., Bizios, R., Conditions which promote mineralization at the bone-implant interface: A model for in vitro study (1996) Biomaterials, 17, pp. 209-215; Anseme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Iost, A., Hardouin, P., Qualitative and quantitative study of human osteoblast adhesion on materials with various surface roughnesses (2000) J Biomed Mater Res, 49, pp. 155-166; Diniz, M.G., Soares, G.A., Coelho, M.J., Fernandes, M.H., Surface topography modulates the osteogenesis in human bone marrow cell cultures grown on titanium samples prepared by a combination of mechanical and acid treatments (2002) J Mater Sci: Mater Med, 13, pp. 421-432; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Min, 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone Min, 17, pp. 15-29
Keywords: 3N; 4-bioglass composite; Adhesion; Adsorption; alkaline phosphatase; article; Biocompatibility; Bioglass; Biomaterials; bone marrow cell; Bone Marrow Cells; Calcium; cell adhesion; Cell Culture Techniques; cell differentiation; Cell Division; cell growth; cell proliferation; composite material; controlled study; culture medium; Dissolution; glass; Growth kinetics; human; Human bone marrow cells; human cell; Humans; immersion; in vitro study; Mechanical properties; MG63 osteoblast-like cells; Microscopy, Electron, Scanning; osteoblast; Osteoblasts; Osteocompatibility; Osteogenic differentiation; phenotype; phosphorus; priority journal; Proteins; rigidity; Si; Silicon compounds; silicon derivative; surface property; tensile strength; Time Factors

Silicon and iron levels in tissues of animals treated with a "ferrimagnetic ceramic" with oncotherapeutic potential (anti-tumor) value - Almeida, T.; Soares, M.E.; Cavalheiro, J.; Bastos, M.D.L. (Journal of Trace Elements in Medicine and BiologyJ. Trace Elem. Med. Biol., 2002)
The stability in a biological environment of an injectable cement with oncotherapeutic potential - consisting of a glass powder of SiO 2 (35.6%), CaO (42.4%), P 2O 5 (17%), Na 2O (5%) and 30% of its weight of Fe 3O 4 dissolved in (NH 4) 2HPO 4 plus NH 4H 2PO 4 - was evaluated referring to the release of silicon and iron. The experimental model was the rat, and organs (liver, kidney, spleen, lung, heart, and brain) of the implanted and control animals were collected for quantification of these elements by electrothermal atomization atomic absorption spectrometry methods. In most of the analysed organs no significant difference in the contents of silicon and iron between the implanted and the control animals was found.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JTEBFdoi: 10.1016/S0946-672X(02)80054-2PubMed ID: 12530589Language of Original Document: EnglishCorrespondence Address: Bastos, M.D.L.; Toxicology Department, Faculty of Pharmacy, University of Porto, Rua Aníbal Cunha 164, 4050 Porto, PortugalChemicals/CAS: calcium oxide, 1305-78-8; iron, 14093-02-8, 53858-86-9, 7439-89-6; phosphorus pentoxide, 1314-56-3; silicon dioxide, 10279-57-9, 14464-46-1, 14808-60-7, 15468-32-3, 60676-86-0, 7631-86-9; silicon, 7440-21-3; Biocompatible Materials; Ceramics; Iron, 7439-89-6; Silicon, 7440-21-3; Tissue ExtractsReferences: Rofstad, E.K., Brustad, T., Primary and secondary cell death in human melanoma xenografts following hyperthermic treatment (1986) Cancer Res., 46, pp. 355-361;Nishimura, Y., Shibamoto, Y., Jo, S., Akuta, K., Hiraoka, M., Takahashi, M., Abe, M., Relationship between heat-induced vascular damage and thermosensitivity in four mouse tumors (1988) Cancer Res., 48, pp. 7226-7230; Brown, S.L., Hunt, J.W., Hill, R.P., Differential thermal sensitivity of tumour and normal tissue microvascular response during hyperthermia (1992) Int. J. Hyperthermia, 8, pp. 501-514; Dudar, T.E., Jain, R.K., Differential response of normal and tumor microcirculation to hyperthermia (1984) Cancer Res., 44, pp. 605-612; Hill, S.A., Smith, K.A., Denekamp, J., Reduced thermal sensitivity of the vasculature in a slowly growing tumour (1989) Int. J. Hyperthermia, 5, pp. 359-370; Bicher, H.I., Hetzel, F.W., Sandhu, T.S., Frinak, S., Vaupel, P., O'Hara, M.D., O'Brien, T., Effects of Hyperthermia on normal and tumor microenvironment (1980) Radiology, 137, pp. 523-530; Song, C.W., Kang, M.S., Rhee, J.G., Levitt, S.H., The effect of hyperthermia on vascular function, pH, and cell survival (1980) Radiology, 137, pp. 795-803; Emami, B., Song, C.W., Physiological mechanisms in hyperthermia: A review (1984) Int. J. Radiation Oncology Biol. Phys., 10, pp. 289-295; Cavalheiro, J., Vasconcelos, M., Afonso, A., Branco, R., Ferrimagnetic and biocompatible cement for tumours thermotherapy (1996) Bioceramics, 9, pp. 243-246; Coury, A.J., Levy, R.J., McMillin, C.R., Pathak, Y., Ratner, B.D., Schoen, F.J., Williams, D.F., Williams, R.L., Degradation of materials in the biological environment (1996) Biomaterials Science, pp. 243-260. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE (Eds). Academic Press, San Diego; Williams, D.F., Williams, R.L., Degradative effects of the biological environment on metals and ceramics (1996) Biomaterials Science, pp. 260-267. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE (Eds). Academic Press, San Diego; Van Dyck, K., Robberecht, H., Van Cauwenbergh, R., Deelstra, H., Arnaud, J., Willemyns, L., Benijts, F., Uytterhoeven, M., Spectrometric determination of silicon in food and biological samples: An interlaboratory trial (2000) J. Anal. At. Spectrom., 15, pp. 735-741; Adler, A.J., Etzion, Z., Berlyne, G.M., Uptake, distribution, and excretion of 31silicon in normal rats (1986) Am. J. Physiol., 251, pp. E670-E673; Beattie, J.H., Avenell, A., Trace element nutrition and bone metabolism (1992) Nutrition Res. Rev., 5, pp. 167-188; Robinson, C.H., Lawler, M.R., Mineral elements (1982) Normal and Therapeutic Nutrition, 16 th Edition, pp. 131-160. , Robinson CH, Lawler MR (Eds). Macmillan Publishing Co., Inc., New York, Collier Macmillan Publishers, London; Sorond, F.A., Ratan, R.R., Ironing-out mechanisms of neuronal injury under hypoxic-ischemic conditions and potential role of iron chelators as neuroprotective agents (2000) Antioxid. Redox Signal, 2, pp. 421-436; Bonkovsky, H.L., Lambrecht, R.W., Iron-induced liver injury (2000) Clin. Liver Dis., 4, pp. 409-429; Bartfay, W.J., Bartfay, E., Iron-overload cardiomyopathy: Evidence for a free radical-mediated mechanism of injury and dysfunction in a murine model (2000) Biol. Res. Nurs., 2, pp. 49-59; Kang, J.L., Pack, I.S., Lee, H.S., Castranova, V., Enhancement of nuclear factor-KB activation and protein tyrosine phosphorylation by a tyrosine phosphatase inhibitor, pervanadate, involves reactive oxygen species in silica-stimulated macrophages (2000) Toxicology, 151, pp. 81-89
Keywords: animal model; animal tissue; Animalia; Animals; article; atomic absorption spectrometry; Biocompatible Materials; calcium oxide; cancer therapy; cement; ceramics; controlled study; experimental model; Ferrimagnetic ceramic; heat; Humans; implant; Iron; Magnetics; materials testing; Neoplasms; nonhuman; Oncotherapy; phosphorus pentoxide; powder; priority journal; Prostheses and Implants; rat; Rats; Reproducibility of Results; Silicon; silicon dioxide; tissue distribution; Tissue Extracts

Structural analysis of Si-substituted hydroxyapatite: Zeta potential and X-ray photoelectron spectroscopy - Botelho, C.M.; Lopes, M.A.; Gibson, I.R.; Best, S.M.; Santos, J.D. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2002)
The aim of this study was to determine the effect of the incorporation of silicon on the surface charge of hydroxyapatite (HA) and to assess surface structural changes of HA and Si-HA induced by dissolution in both static and dynamic systems. X-ray photoelectron spectroscopy (XPS) analysis showed that SiO 4 4- groups were substituted for PO 4 3- groups in the silicon-hydroxyapatite (Si-HA) lattice according to a previously proposed substitution mechanism without the formation of other crystalline phases, such as tricalcium phosphate or calcium oxide. The substituted silicon induced a decrease in the net surface charge and the isoelectric point of HA as determined by zeta potential (ZP) measurements. At physiological pH = 7.4 the surface charge of Si-HA was significantly lowered compared to unmodified HA, i.e. -50 ±5 to - 71 ± 5 eV, caused by the presence of silicate groups in the HA lattice, which may account for a faster in vitro apatite formation using SBF testing. XPS results indicated that silicon seems to be preferentially leached out from Si-HA surface compared to other ionic species after dissolution studies in tris-buffer using a dynamic system. © 2002 Kluwer Academic Publishers.
Cited By (since 1996): 59Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1021177601899Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB - Inst. de Engenharia Biomedica, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: calcium oxide, 1305-78-8; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; phosphate, 14066-19-4, 14265-44-2; silicon, 7440-21-3Tradenames: Philips PW1606 spectrometer, Philips; Siemens D5000 X ray diffractometer, Siemens; Sotax CE6Manufacturers: Philips; SiemensReferences: Carlisle, E.M., (1984) Fed. Proc., 43, p. 680;Carlisle, E.M., (1986) Silicon Biochemistry, , edited by D. Evered and M. O'Connor (Wiley, New York); Schwarz, K., (1978) Biochemistry of Silicon and Related Problems, pp. 207-230. , edited by G. Bendz and I. Lindqvist (Plenum Press, New York); Schwarz, K., Milne, D.B., (1972) Nature, 239, p. 333; Voronkov, M.G., Skorobogatova, V.I., Vugmeister, E.K., Makarskii, V., (1975) Doklady Biochemistry, 222, p. 29; Hench, L.L., (1999) Biological Implications, pp. 116-163; Keeting, P.E., Oursler, M.J., Weigand, K.E., Bonds, S.K., Spelsberg, T.S., Riggs, B.L., (1992) J. Bone Mineral Res., 7, p. 1281; Hench, L.L., (1982) J. Phys., 43, p. 625; Hench, L.L., (1991) J. Am. Ceram. Soc., 74, p. 1487; Hench, L.L., Wilson, J., (1999) An Introduction to Bioceramics, , World Scientific Publishing Co., Singapore; Jha, L.J., Best, S., Santos, J.D., Gibson, I.R., Bonfield, W., Silicon-Substituted Apatites and Process for the Preparation Thereof, , Worldwide Patent, PCT/GB97/02325 and US Patent Serial No 09/147773 (1999); Gibson, I.R., Best, S.M., Bonfield, W., (1999) J. Biomed. Mat. Res., 44, p. 422; Gibson, I.R., Huang, J., Best, S.M., Bonfield, W., (1999) Bioceramics, Vol. 12, Proceedings of the 12th International Symposium on Ceramics in Medicine (Nara, Japan November 1999), 12, pp. 191-194. , edited by H. Ohgushi, G. W. Hastings and T. Yoshikawa (World Scientific Publishing Co., London); Gibson, I.R., Hing, K.A., Revell, P.A., Santos, J.D., Best, S.M., Bonfield, W., (2002) Key Engin. Mat., 218-222, p. 203; Maroudas, N.G., (1975) J. Theoret. Biol., 49, p. 417; Van Wachem, P.B., Hogt, A.H., Beueling, T., (1987) Biomaterials, 8, p. 323; Davies, J.E., (1998) Surface Characterization of Biomaterials, pp. 219-234. , edited by B. D. Ratner (Elsevier, Amsterdam); Shelton, R.M., Rasmussen, A.C., Davies, J.E., (1988) Biomaterials, 9, p. 24; Ducheyne, P., Beight, J., Cuckler, J., Evans, B., Radin, S., (1990) Biomaterials, 11, p. 531; Ohgushi, H., Goldberg, V.M., Caplan, A.I., (1989) J. Orthop. Res., 7, p. 568; Daculsi, G., Le Geros, R.Z., Nery, E., Lynch, K., Kerebel, B., (1989) J. Biomed. Mater. Res., 23, p. 883; Hyakuna, K., Yamamuro, T., Kotoura, Y., Kakutani, Y., Kitsugi, T., Takagi, H., Oka, M., Kokubo, T., (1989) J. Biomed. Mater. Res., 23, p. 1049; Kotoura, Y., Yamamuro, T., Shikata, J., Kakutani, Y., Kitsugi, T., Hyakuna, K., Tanaka, H., (1986) Orthop. Res. Sci., 13, p. 633; Fujiu, T., Ogino, M., (1984) J. Biomed. Mater. Res., 18, p. 845; Rehman, I., Bonfield, W., (1997) J. Mat. Sci.: Mater. in Med., 8, p. 1; Nyquist, R.A., Putzig, C.L., Leugers, M.A., (1995) Infrared and Raman Spectral Atlas of Inorganic Compounds and Organic Salts, 3; NIST - National Institute of Standards and Technology Database; Van Raemdonck, W., Ducheyne, P., De Meester, P., (1984) Metal and Ceramic Biomaterials, pp. 143-146. , CRC Press; Gibson, I.R., Jha, L.J., Santos, J.D., Best, S.M., Bonfield, W., (1998) Bioceramics, Vol. 11, Proceedings of the 11th International Symposium on Ceramics in Medicine (New York, NY, USA, November 1998), , edited by R. Z. LeGeros and J. P. LeGeros (World Scientific Publishing Co., USA)
Keywords: calcium oxide; calcium phosphate; Chemical modification; conference paper; crystal structure; Dissolution; Electric Potential; electricity; hydroxyapatite; in vitro study; isoelectric point; Lime; molecular dynamics; pH; pH measurement; phase transition; phosphate; Phosphorus Compounds; priority journal; reaction analysis; Silicon; Silicon compounds; silicon derivative; structure analysis; surface property; X ray photoelectron spectroscopy; Zeta potential

Wettability and surface charge of Si 3N 4-bioglass composites in contact with simulated physiological liquids - Amaral, M.; Lopes, M.A.; Santos, J.D.; Silva, R.F. (BiomaterialsBiomaterials, 2002)
Wettability and surface charge studies were performed on a novel Si 3N 4-30wt% bioglass biocomposite. Contact angle and surface tension variation with time were determined at 25°C, respectively, by the sessile and pendant drop techniques, for distinct testing liquids: water, diiodomethane, simulated body fluid (SBF) and bovine serum albumin (BSA) dissolved in SBF solution. This biocomposite revealed a hydrophilic character (θ=26.6±2.0°) and a surface tension value (66.6mJm
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(02)00155-2Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratório de Biomateriais, Inst. de Engenharia Biomedica (INEB), Rua do Campo Alegre, 823, 4150 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Serum Albumin, Bovine; Silicon Compounds; silicon nitride, 12033-89-5References: Von Recum, A.F., (1999) Handbook of biomaterials evaluation: scientific, technical, and clinical testing of implant materials, 2nd. ed., , Hemisphere Pub;Davies, J.E., The importance and measurement of surface charge species in cell behaviour at the biomaterial interface (1998) Surface characterisation of biomaterials, 6, pp. 219-234. , Ratner, editor. Progress in Biomedical Engineering. Amsterdam: Elsevier; Lampin, M., Warocquier-Clérout, R., Legris, C., Degrange, M., Sigot-Luizard, M.F., Correlation between substratum roughness and wettability, cell adhesion, and cell migration (1997) J Biomed Mater Res, 36, pp. 99-108; Dewez, J.L., Schneider, Y.J., Rouxhet, P.G., Coupled influence of substratum hydrophilicity and surfactant on epithelial cell adhesion (1996) J Biomed Mater Res, 30, pp. 373-383; Hallab, N.J., Bundy, K., O'Connor, R., Clark, R., Moses, R.L., Cell adhesion to biomaterials: Correlations between surface charge, surface roughness, adsorbed protein, and cell morphology (1995) J Long-Term Effects Med Implants, 3, pp. 209-231; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 7, pp. 667-681; Garbassi, Morra, Occhiello, Polymer surfaces, from physics to technology, , Wiley & Sons, New York [Chapter 4]; Adamson, A.W., (1990) Physical chemistry of surfaces, , 5th ed, New York: Wiley; Correia, N.T., Ramos, J.M., Saramago, B., Calado, J., Estimation of the surface tension of a solid: Application to a liquid crystalline (1997) J Colloid Interface Sci, 189, pp. 361-369; Schrader, M.E., Young-Dupre Revisited (1995) Langmuir, 11, pp. 3585-3589; Nishizawa, K., Toriyama, M., Effects of the surface wettability and zeta potential of bioceramics on the adhesiveness of anchorage-dependent animal-cells (1993) J Ferment Bioeng, 6, pp. 435-437; Suzuki, T., Nishizawa, K., Yokogawa, Y., Kameyama, T., Time-dependent variation of the surface structure of bioceramics in tissue culture medium and the effect on adhesiveness of cells (1996) J Ferment Bioeng, 3, pp. 226-232; Parfitt, G.D., (1967) Principles of the colloidal state, , London: Royal Institute of Chemistry; Hench, L.L., Biomaterials: A forecast for the future (1998) Biomaterials, 19, pp. 1419-1423; Radin, S., Ducheyne, P., Falaize, S., Hammond, A., In vitro transformation of bioactive glass granules into Ca-P shells (2000) J Biomed Mater Res, 49, pp. 264-272; Amaral, M., Lopes, M.A., Silva, R.F., Santos, J.D., Densification route and mechanical properties of Si3N4-bioglass biocomposites (2002) Biomaterials, 23, pp. 857-862; Santos, J.D., Amaral, M., Oliveira, S.M., Lopes, M.A., Silva, R.F., Silicon nitride-bioglass ® composite for biomedical applications (2001) Key Eng Mater, 192-195, pp. 589-592; Krajewski, A., Piancastelli, A., Malavolti, R., Albumin adhesion on ceramics and correlation with their Z-potential (1998) Biomaterials, 19, pp. 637-641; Kokubo, T., Kushitani, H., Ohtsuki, C., Sakka, S., Chemical reaction of bioactive glass and glass-ceramics with a simulated body fluid (1992) J Mater Sci: Mater Med, 3, pp. 79-83; Vogler, E.A., Interfacial chemistry in biomaterials science (1993) Wettability, surfactant science series, 49, pp. 183-250. , Berg J.C., editor, Chapter 4; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tension, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Ferraz, M.P., Monteiro, F.J., Serro, A.P., Saramago, B., Gibson, I.R., Santos, J.D., Effect of chemical composition on hydrophobicity and zeta potential of plasma sprayed HA/CaO-P 2O 5 glass coatings (2001) Biomaterials, 22, pp. 3105-3112; Agathopoulos, S., Nikolopoulos, P., Wettability and interfacial interactions in bioceramic-body-liquid systems (1995) J Biomed Mater Res, 29, pp. 421-429; Agathopoulos, S., Nikolopoulos, P., Determination of the energy of the interactions between oxides and biological liquids (1995) Fourth Euro ceramics, 8, pp. 319-324. , A. Ravaglioli; Wang, L., Sigmund, W., Aldinger, F., Systematic approach for dispersion of silicon nitride powder in organic media: I, surface chemistry of the powder (2000) J Am Ceram Soc, 4, pp. 691-696; Galassi, C., Bertoni, F., Water-based Si 3N 4 suspensions: Part I effect of processing routes on the surface chemistry and particle interactions (2000) J Mater Res, 1, pp. 155-163; Haynes, C.A., Norde, W., Globular proteins at solid/liquid interfaces (1994) Colloids Surf B: Biointerfaces, 2, pp. 517-566
Keywords: 3N; 4-bioglass composites; Adsorption; aqueous solution; article; Biocomposites; Biomaterials; body fluid; Body fluids; Bovinae; bovine serum albumin; cation; Cattle; ceramics; chemistry; conformation; Conformations; Contact angle; electrochemistry; enthalpy; entropy; glass; Glass ceramics; Hydrogen-Ion Concentration; hydrophilicity; liquid; methyl iodide; methylene iodide; pH; Physiological models; priority journal; Serum Albumin; Serum Albumin, Bovine; Si; Silicon compounds; silicon derivative; Silicon nitride; simulation; Support, Non-U.S. Gov't; Surface charge; Surface chemistry; Surface Properties; surface property; Surface tension; temperature; time; unclassified drug; Water; wettability; Wetting; Zeta potential

Adsorption and release studies of sodium ampicillin from hydroxyapatite and glass-reinforced hydroxyapatite composites - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J.; Gibson, I.R.; Knowles, J.C. (BiomaterialsBiomaterials, 2001)
As a potential therapy for periodontitis, sodium ampicillin, a broad spectrum antibiotic, was adsorbed onto hydroxyapatite (HA) and glass-reinforced hydroxyaptite (GR-HA) composites, and was subsequently released in vitro. The sodium ampicillin, was adsorbed more on HA compared to the GR-HA composites. X-ray diffraction (XRD) and Rietveld analysis were used to identify and quantify the levels of HA and β-tricalcium phosphate (β-TCP) in the microstructure of the GR-HA composites. Lattice parameters changes were observed for the β-TCP phase dependant on the amount of glass added. The release kinetics were shown to be divided into three stages, the first of which where a large amount of sodium ampicillin is released, followed by a slower release rate and then a final stage where the release amount approaches zero, until no more sodium ampicillin was present. X-ray photoeletron spectroscopy (XPS) studies were carried out in order to ensure that the entire antibiotic adsorbed onto the materials had been released. These kinetics studies have indicated the possibility of using these materials as possible carriers for drug delivery. Copyright © 2001 Elsevier Science Ltd.
Cited By (since 1996): 55Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(00)00296-9PubMed ID: 11336313Language of Original Document: EnglishCorrespondence Address: Knowles, J.C.; Department of Biomaterials, Eastman Dental Institute, University College London, 256 Gray's Inn Road, London WC1X 8LD, United Kingdom; email: j.knowles@eastman.ucl.ac.ukChemicals/CAS: Ampicillin, 69-53-4; Durapatite, 1306-06-5; PenicillinsManufacturers: Plasma Biotal, United KingdomReferences: Farag, S.A., Simultaneous liquid chromatographic analysis of the β-lactam antibiotics cefazolin, cefadroxil, cepalexin, ampicillin, and cephradine in solution (1998) J AOAC Int, 81, pp. 381-385;Somayaji, B.V., Jariwala, U., Jayachandran, P., Vidyalakshmi, K., Dudhani, R.V., Evaluation of antimicrobial efficacy and release pattern of tetracycline and metronidazole using a local delivery system (1998) J Periodontol, 69, pp. 409-413; Soskolne, W.A., Heasman, P.A., Stabholz, A., Smart, G.J., Palmer, M., Flashner, M., Newman, H.N., Sustained local delivery of chlorhexidine in the treatment of periodontitis; a multi-center study (1997) J Periodontol, 68, pp. 32-38; Steinberg, D., Friedman, M., Soskolne, A., Sela, M.N., A new degradable controlled release device for treatment of periodontal disease; in vitro release study (1990) J Periodontol, 61, pp. 393-398; Stoltze, K., Concentration of metronidazole in periodontal pockets after application of a metronidazole 25% dental gel (1992) J Clin Periodontol, 19, pp. 698-701; Ramaglia, L., Sbordone, L., Lenci, F., Gulletta, E., Amato, G., Kennedy, E.B., Microbiology of porous hydroxylapatite implants in human periodontal osseous defects (1986) Biomaterials and clinical applications, 7 vol., pp. 675-680. , Pizzoferrate A., Marachetti P.G., Ravaglioli A., Lee A.J.C. (Eds.), Netherlands: Elsevier; Wilson, J., Low, S., Fetner, A., Hench, L.L., Bioactive materials for periodontal treatment; a comparative study (1986) Biomaterials and clinical applications, 7 vol., pp. 223-228. , Pizzoferrate A., Marachetti P.G., Ravaglioli A., Lee A.J.C. (Eds.), Netherlands: Elsevier; Kenney, E.B., Lekovic, V., Sa Ferreira, J.C., Han, T., Dimitrijavic, B., Carranza F.A. Jr, Bone formation within porous hydroxyapatite implants in human periodontal defects (1986) J Periodontol, 57, pp. 76-83; Krejei, C.B., Bissada, N.F., Farah, C., Greenwell, H., Clinical evaluation of porous and nonporous hydroxyapatite in treatment of human periodontal bony defects (1987) J Periodontol, 58, pp. 521-528; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tensions, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Santos, J.D., Silva, P.L., Knowles, J.C., Talal, S., Monteiro, F.J., Reinforcement of hydroxyapatite by adding P 2O 5-CaO glasses with Na 2O, K 2O, MgO (1996) J Mater Sci Mater Med, 7, pp. 187-189; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., Osteocompatibility and in vivo evaluation of glass reinforced hydroxyapatite composites (1999) Bioceramics, 12 vol., pp. 421-424. , Ohgushi H., Hastings G.W., Yoshikawa T. (Eds.), Japan: World Scientific; Santos, J.D., Vasconcelos, M., Reis, R.L., Afonso, A., Monteiro, F.J., Hastings, G.W., Glass reinforced hydroxyapatite composites; physical properties and preliminary histological studies in rabbits (1994) Bioceramics, 7 vol., pp. 243-248. , Andersson O.H., Yli-Urpo A. (Eds.), Finland: Pergamon Press; Klein, C.P.A.T., Wolke, J.G.C., de Blieck-Hogervorst, J.M.A., de Groot, K., Features of calcium phosphate plasma-sprayed coatings; an in vitro study (1994) J Biomed Mater Res, 28, pp. 961-967; Klein, C.P.A.T., Wolke, J.G.C., de Blieck-Hogervorst, J.M.A., de Groot, K., Calcium phosphate plasma-sprayed coatings and their stability; an in vivo study (1994) J Biomed Mater Res, 28, pp. 909-917; Langnbucher, F., Benz, D., Kürth, W., Möller, H., Otz, M., Standardized Flow-cell method as an alternative to existing pharmacopoeial dissolution testing (1989) Pharm Ind, 51, pp. 1276-1281; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterization of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass-reinforced hydroxyapatite; a comprehensive study of the effect of glass composition on crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Thomas M. Ultraviolet and visible spectroscopy, second edition. In: Ando DJ, editor. England: Wiley, 1996. p. 16-30Itokazu, M., Itoh, Y., Fukuta, M., Miyamato, K., Ohara, A., Oshima, K., Nishimoto, Y., Shimizu, K., Treatment of osteomyelitis by using antibiotic loaded porous ceramic (1999) Bioceramics, 12 vol., pp. 3-6. , Ohgushi H., Hastings G.W., Yoshikawa T. (Eds.), Japan: World Scientific; Shinto, Y., Uchida, A., Korkusuz, F., Araki, N., Ono, K., Calcium hydroxyapatite ceramic used as a delivery system for antibiotics (1992) J Bone Jt Surg, 74 B, pp. 600-604; Downes, S., Clifford, C.J., Scotchford, C., Klein, C.P.A.T., Comparison of the release of growth hormone from hydroxyapatite, heat-treated hydroxyapatite, and fluoroapatite coatings on titanium (1995) J Biomed Mater Res, 29, pp. 1053-1060; Curtis, M.A., Griffiths, G.S., Johnson, N.W., The total protein concentration of gingival crevicular fluid. Variation with sampling time and gingival inflammation (1988) J Clin Periondontol, 15, pp. 628-632; Stoltze K. Concentration of metronidazole in periodontal pockets after application of a metronidazole 25% dental gel. J Clin Periondontol 1992, 689-701Jones, A.A., Koenman, K.S., Newbold, D.A., Manwell, M.A., Clinical and microbiological effects of controlled release locally delivered minocycline in periodontitis (1994) J Periodontol, 65, pp. 1058-1066
Keywords: Adsorption; ampicillin; Antibiotics; article; calcium phosphate; composite material; controlled study; drug adsorption; Drug delivery; drug delivery system; Drug release; Durapatite; glass; Glass-reinforced hydroxyapatite; hydroxyapatite; Kinetics; Microstructure; Penicillins; periodontitis; priority journal; Reinforcement; Rietveld analysis; roentgen spectroscopy; Sodium ampicillin; Sodium compounds; structure analysis; unclassified drug; X ray diffraction; X ray diffraction analysis; X ray photoelectron spectroscopy; X-Ray Diffraction

CaO-P 2O 5 glass ceramics containing bioactive phases: crystallisation and in vitro bioactivity studies - Zhang, Y.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2001)
CaO-P 2O 5 glass ceramics were prepared using a two-step heat treatment of nucleation and crystal growth using TiO 2 and Na 2O as nucleating agents. X-ray diffraction analysis demonstrated that bioactive and bioresorbable crystalline phases were precipitated in the microstructure, depending upon the relative content of the additives and of the CaO/P 2O 5 ratio of the glass. Ca 2P 2O 7 (β-DCP) was the main crystalline phase however β-Ca 3(PO 4) 2 (β-TCP), could also be formed by increasing the content of TiO 2 and the CaO/P 2O 5 ratio. Na and Ti-containing phases, CaTi 4(PO 4) 6, and/or NaTi 2(PO 4) 3, could also be assigned in the XRD spectra. In vitro testing in simulated body fluid (SBF) has proved the in vitro bioactivity of these glass ceramics with the formation of Ca-deficient apatite crystals, as demonstrated by Scanning Electron Microscopy (SEM) and X-ray photoelectron spectroscopy (XPS) analyses.
Conference code: 57760Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Zhang, Y.; Instituto de Engenharia Biomedica, (INEB), Porto, PortugalReferences: Hench, L.L., (1991) J. Am. Ceram. Soc., 74, p. 1487;Kokubo, T., (1993) An Introduction to Bioceramics, p. 75. , L.L. Hench and J.Wilson, Eds., World Scientific Singapore; Abe, Y., Naruse, A., Hosoe, M., Fukui, H., Hasegawa, J., (1975) The 1975 Symposium of Biomaterials, p. 202. , Kyoto; Reaney, I.M., James, P.F., Lee, W.E., (1996) J. Am. Ceram. Soc., Science, 79, pp. 1934-1944; Kasuga, T., Abe, Y., (1998) J. Mater. Res., 13, p. 1; Vogel, J., Schulze, K.J., Reif, D., Hartmann, P., Platzbecker, U., Leuner, B., (1997) Bioceramics, 10, p. 57. , L. Sedel and C. Rey, Eds., Elsevier Science; Hosono, H., Zhang, Z., Abe, Y., (1989) J. Am. Ceram. Soc., 72, p. 1587; Zhang, Y., Santos, J.D., Journal of the European Ceramic Society, , In press
Keywords: Bioactivity; Biomaterials; Ceramic materials; Crystal growth; Crystal microstructure; Crystalline materials; Crystalline phase; Crystallization; glass; Lime; Nucleating agents; Nucleation; Phosphates; Scanning electron microscopy; Simulated body fluid; X ray diffraction analysis; X ray photoelectron spectroscopy

Effect of chemical composition on hydrophobicity and zeta potential of plasma sprayed HA/CaO-P 2O 5 glass coatings - Ferraz, M.P.; Monteiro, F.J.; Serro, A.P.; Saramago, B.; Gibson, I.R.; Santos, J.D. (BiomaterialsBiomaterials, 2001)
Multilayered plasma sprayed coatings on the surface of Ti-6Al-4V alloys have been prepared, which were composed of an underlayer of HA and a surface layer of a CaO-P 2O 5 glass-HA composite, with 2 or 4 wt% of glass. Contact angle and surface tension variation with time, for both water and a protein solution, were determined by the sessile and pendent drop methods respectively using the ADSA-P software. Wettability studies showed that hydrophobicity of the coatings increase with the glass addition. The work of adhesion of albumin was also altered in a controlled manner by the addition of the CaO-P 2O 5 glass, being lower on the composite coatings than on HA. Zeta potential (ZP) results showed that composite coatings presented a higher net negative charge than HA coatings and that ZP values were also influenced by the content of the glass. This study demonstrated that the surface properties of those coatings may be modified by the addition of CaO-P 2O 5 glass. © 2001 Published by Elsevier Science Ltd.
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(01)00059-XPubMed ID: 11603581Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratório de Biomateriais, Inst. de Engenharia Biomedica (INEB), Rua do Campo Alegre 823, 4150 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Calcium Compounds; Durapatite, 1306-06-5; lime, 1305-78-8; Oxides; Phosphorus Compounds; phosphorus pentoxide, 1314-56-3; Serum Albumin, BovineReferences: Klein, C.P.A.T., Patka, P., Van der Lubbe, H.B.M., Plasma-sprayed coatings of tetracalciumphosphate, hydroxyl-apatite, and α-TCP on titanium alloy: An interface study (1991) J Biomed Mater Res, 25, pp. 53-65;Jansen, J.A., Van der Waerden, J.P., Wolke, J.G., Histologic investigation of the biologic behavior of different hydroxyapatite plasma-sprayed coatings in rabbits (1993) J Biomed Mater Res, 14, pp. 603-610; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., Comparative biological properties of HA plasma-sprayed coatings having different crystallinities (1994) J Mater Sci: Mater Med, 5, pp. 11-17; Courteney-Harris, R.G., Kayser, M.V., Downes, S., Comparison of the early production of extracellular matrix on dense hydroxyapatite and hydroxyapatite-coated titanium in cell and organ culture (1995) Biomaterials, 16, pp. 489-495; Labat, B., Chanson, A., Frey, J., Effects of γ-alumina and hydroxyapatite coatings on the growth and metabolism of human osteoblasts (1995) J Biomed Mater Res, 29, pp. 1397-1401; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., Adult human bone cells derived from jaw bones cultured on plasma-sprayed or polished surfaces to titanium or hydroxyapatite discs (1996) J Mater Sci: Mater Med, 7, pp. 21-28; Silva, P.L., Santos, J.D., Monteiro, F.J., Knowles, J.C., Adhesion and microstructural characterisation of plasma-sprayed hydroxyapatite/glass ceramic coatings onto Ti-6Al-4V substrates (1998) Surf Coating Technol, 102, pp. 191-196; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P 2O 5 glass hydroxyapatite double-layer plasma-sprayed coating: In vitro bioactivity evaluation (1999) J Biomed Mater Res, 45, pp. 376-383; Ferraz, M.P., Fernandes, M.H., Trigo Cabral, A., Santos, J.D., Monteiro, F.J., In vitro growth and differentiation of osteoblast-like human bone marrow cells on glass reinforced HA plasma-sprayed coatings (1999) J Mater Sci: Mater Med, 10 (9), pp. 567-576; Lapin, M., Warocquier-Clérout, R., Legris, C., Degrange, M., Luizard, M.F.S., Correlation between roughness and wettability, cell adhesion and cell migration (1997) J Biomed Mater Res, 36, pp. 99-108; Williams, D.F., (1982) Fundamental aspects of biocompatibility, , Boca Raton: CRC Press; Adamson, W., (1990) Physical chemistry of surfaces, 5th ed., , New York: Wiley; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions: Structure and properties of the composites (1995) J Mater Sci: Mater Med, 6, pp. 348-352; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass-reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Chen, P., Li, D., Boruvka, L., Rotenberg, Y., Neumann, A.W., Automation of axisymmetric drop shape analysis for measurements of interfacial tensions and contact angles (1990) Coll and Surf, 43, pp. 151-197; Cheng, P., Neumann, A.W., Computational evaluation of axisymmetric drop shape analysis-profile (ASA-P) (1992) Coll and Surf, 62, pp. 297-306; Young, T., (1835) Miscellaneous works, 1, p. 418. , Peacock G, editor. London: Murray; Schrader, M.E., Young Dupré revisited (1995) Langmuir, 11, p. 3585; Owens, D.K., Wendt, R.D., Estimation of the surface free energy of polymers (1969) J Appl Polym Sci, 13, pp. 1741-1769; Williams, R.L., Williams, D.F., Albumin adsorption on metal surfaces (1988) Biomaterials, 9, pp. 206-212; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tension, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Tripp, B.C., Magda, J.J., Andrade, J.D., Adsorption of globular proteins at the air/water interface as measured via dynamic surface tension: Concentration dependence, mass-transfer and adsorption kinetics (1995) J Coll Interface Sci, 173, pp. 16-27; Voigt, A., Thiel, O., Williams, D., Policova, Z., Zing, W., Neumann, A.W., Axisymmetric drop shape analysis (ADSA) applied to protein solutions (1991) Coll and Surf, 58, pp. 315-326; Suzuki, T., Nishizawa, K., Yokogawa, Y., Kameyama, T., Time-dependent variation of the surface structure of bioceramics in tissue culture medium and the effect of adhesiveness of cells (1996) J Ferment Bioeng, 81, pp. 226-232; Susuki, T., Yamamoto, T., Yoriyama, M., Kameyama, T., Surface instability of calcium phosphate ceramics in tissue culture medium and the effect on adhesion and growth of anchorage-dependent animal cells (1997) J Biomed Mater Res, 34, pp. 504-517; Haynes, C.A., Norde, W., Globular proteins at solid/liquid interfaces (1994) Coll and Surf B: Biointerfaces, 2, pp. 517-566; Kondori, K., Soito, M., Takebe, T., Yasukawa, A., Adsorption of bovine serum albumin on synthetic carbonate calcium hydroxyapatite (1995) J Coll Interface Sci, 184, pp. 124-129
Keywords: Adhesion; alloy; analytic method; article; bovine serum albumin; Calcium Compounds; calcium oxide; chemical composition; Chemical modification; Coatings; Composition; computer program; Contact angle; Durapatite; glass; hydrophobicity; hydroxyapatite; Hydroxyapatite glass composites; oxide; Oxides; pentoxide; Phosphorus Compounds; priority journal; protein; Serum Albumin, Bovine; Sprayed coatings; Surface charge; Surface Properties; Surface tension; Surface tension zeta potential; time; unclassified drug; Water; wettability; Wetting; X-Ray Diffraction; Zeta potential

HA and double-layer HA-P 2O 5/CaO glass coatings: Influence of chemical composition on human bone marrow cells osteoblastic behavior - Ferraz, M.P.; Fernandes, M.H.; Santos, J.D.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2001)
Human osteoblastic bone marrow derived cells were cultured for 28 days onto the surface of a glass reinforced hydroxyapatite (HA) composite and a commercial type HA plasma sprayed coatings, both in the "as-received" condition and after an immersion treatment with culture medium during 21 days. Cell proliferation and differentiation were analyzed as a function of the chemical composition of the coatings and the immersion treatment. Cell attachment, growth and differentiation of osteoblastic bone marrow cells seeded onto "as-received" plasma sprayed coatings were strongly affected by the time-dependent variation of the surface structure occurring during the first hours of culture. Initial interactions leading to higher amounts of adsorbed protein and zeta potential shifts towards negative charges appeared to result in surface structures with better biological performance. Cultures grown onto the pretreated coatings showed higher rate of cell proliferation and increased functional activity, as compared to those grown onto the corresponding "as-received" materials. However, the cell behavior was similar in the glass composite and HA coatings. The results showed that the glass composites present better characteristics for bone cell growth and function than HA. In addition, this work also provide evidence that the biological performance of the glass composites can be modulated and improved by manipulations in the chemical composition, namely in the content of glass added to HA. © 2001 Kluwer Academic Publishers.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1011245828046Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Rua Dr. Manuel Pereira da Silva, 4200 Porto, PortugalReferences: Klein, C.P.A.T., Patka, P., Van der Lubbe, H.B.M., (1991) J. Biomed. Mater. Res., 25, p. 53;Jansen, J.A., Van Der Waerden, J.P.C.M., Wolke, J.G.C., (1993) J. Mater. Sci Mater. Med., 4, p. 466; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., (1994) J. Mater. Sci. Mater. Med., 5, p. 11; Courteney-Harris, R.G., Kayser, M.V., Downes, S., (1995) Biomaterials, 16, p. 489; Labat, B., Chanson, A., Frey, J., (1995) J. Biomed. Mater. Res., 29, p. 1397; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., (1996) J. Mater. Sci. Mater. Med., 7, p. 21; Ferraz, M.P., Fernandes, M.H., Trigo Cabral, A., Santos, J.D., Monteiro, F.J., (1999) J. Mater. Sci: Mater. Med., 10, p. 567; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mat. Res., 45, p. 376; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 47, p. 603; Anselme, K., Sharrock, P., Hardouin, P., Dard, M., (1997) J. Biomed. Mat. Res., 34, p. 247; Ong, J.L., Prince, C.W., Lucas, L.C., (1995) J. Biomed. Mat. Res., 29, p. 165; Gregoire, M., Orly, I., Kerebel, L.-M., Kerebel, B., (1987) Biol. Cell., 255, p. 59; Morgan, J., Holtman, K., Stanford, C., (1995) J. Dent. Res., 74, p. 190; Chou, L., Firth, J.D., Uitto, V.-J., Brunette, D.M., (1995) J. Cell. Sci., 108, p. 1563; Chou, L., Marek, B., Wagner, W.R., (1999) Biomaterials, 20, p. 977; Susuki, T., Nishizawa, K., Yokogawa, Y., Nagata, F., Kawamoto, Y., Kameyama, T., (1996) J. Ferment. Bioeng., 81, p. 226; Lampin, M., Warocquier-Clerout, R., Legris, C., Degrange, M., Sigot-Luizard, M.F., (1997) J. Biomed. Mater. Res., 36, p. 99; Best, S., Sim, B., Kayser, M., Downes, S., (1997) J. Mater. Sci. Mater. Med., 8; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., (1999) J. Mater. Sci. Mater. Med., 10, p. 663; Maniatopoulos, C., Sodek, J., Melcher, A., (1988) Cell Tissue Res., 254, p. 317; Gundle, R., Joyner, C.Y., Triffit, J.T., (1995) Bone, 16, p. 597; Fernandes, M.H., Costa, M.A., Carvalho, G.S., (1997) J. Mater. Sci. Mater. Med., 8, p. 61; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., (1997) J. Mater. Sci. Mater. Med., 8, p. 233; Fernandes, M.H., (1999) J. Biomat. App., 14, p. 113; Martin, T.J., Findlay, D.M., Heath, J.K., Ng, K.W., (1993) Handbook of Experimental Pharmacology, p. 149. , edited by J. R. Mundy and T. J. Martin (Springer-Verlag, Berlin); Stein, G.S., Lian, J.B., (1993) Cellular and Molecular Biology of Bone, p. 47. , edited by M. Noda (Academic Press Inc., Tokyo); Coelho, M.J., Trigo Cabral, A., Fernandes, M.H., Biomaterials, , in press; Coelho, M.J., Fernandes, M.H., Biomaterials, , in press; Anderson, H.C., Morris, D.C., (1993) Handbook of Experimental Pharmacology, p. 267. , edited by J. R. Mundy and T. J. Martin (Springer-Verlag, Berlin); Krajewski, A., Piancastelli, A., Malavolti, R., (1998) Biomaterials, 19, p. 637; Krajewski, A., Malavolti, R., Piancastelli, A., (1996) Biomaterials, 17, p. 53; Ducheyne, P., Kim, C.S., Pollack, S.R., (1992) J. Biomed. Mater. Res., 26, p. 147; Susuki, T., Yamamoto, T., Toriyama, M., Nishizawa, K., Yokogawa, Y., Mucalo, M.R., Kawamoto, Y., Kameyama, T., (1997) J. Biomed. Mater. Res., 34, p. 507; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Biomaterials, , in press; Kokubo, T., (1993) Bone-Bonding Biomaterals, p. 31. , edited by P. Ducheyne, T. Kokubo and C. A. Blitterswijk (Reed Health-Care Communications, Leiden, The Netherlands); Daculsi, G., Legeros, R.Z., Henghebaert, M., Barbieux, I., (1990) Calcif. Tissue Int., 46, pp. 20-27; Bagambisa, F.B., Joos, U., Schilli, W., (1993) J. Biomed. Mat. Res., 27, pp. 1047-1055; De Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., (1995) J. Biomed. Mat. Res., 29, pp. 89-99; Gwynn, I.A.P., (1994) J. Mater. Sci. Mater Med., 5, pp. 357-360; Ghannam, E.L., Ducheyne, P., Spapiro, I., (1995) J. Biomed Mat. Res., 29, pp. 359-370; Kirkpatrick, C.J., Wagner, M., Kohler, H., Bittinger, F., Otto, M., Klein, C.L., (1997) J. Mater. Sci. Mater Med., 8, pp. 131-141; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., J. Biomed. Mater. Res., , in press
Keywords: Adsorption; alkaline phosphatase; article; Biomedical engineering; Bone; bone marrow; bone marrow cell; Calcium; calcium oxide; cell adhesion; Cell culture; cell differentiation; cell growth; cell proliferation; chemical composition; Coatings; controlled study; culture medium; enzyme activity; glass; Growth kinetics; human; human cell; hydroxyapatite; immersion; osteoblast; oxygen; performance; phosphorus; priority journal; protein binding; protein content; Proteins; Scanning electron microscopy; Surface charge; surface property; time; X ray diffraction

Histological studies of double layer HA/CaO-P 2O 5 glass plasma sprayed coatings using Rabbit model - Ferraz, M.P.; Santos, J.D.; Afonso, A.; Vasconcelos, M.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2001)
The in vivo biological performance of a double layer HA/CaO-P 2O 5 glass and HA plasma sprayed coatings was assessed, using cylindrical implants that were placed in rabbits tibiae and histologically characterised after 2, 4, 8 and 16 weeks of implantation. For both types of coatings, long-term histological results indicated successful contact between implanted materials and bone, with organised new bone established at the interface. The main difference between the two coatings corresponded to the shorter implantation periods, where the composite coating induced faster osteointegration than HA coating. The faster formation of organised bone for composite coatings is discussed in terms of the presence of phase composition in the coatings structure.
Conference code: 57760Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Ferraz, M.P.; Instituto de Engenharia Biomedica, (INEB), Porto, PortugalReferences: Lacefield, W.R., (1988) Bioceramics: Material Characteristics Versus In Vivo Behaviour, pp. 72-80. , P. Ducheyne, J.E. Lemons. New York: New York Academy of Science Publishers;Klein, C.P.A.T., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., (1994) J Biomed Mater Res, 28, pp. 961-967; Klein, C.P.A.T., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., (1994) J Biomed Mater Res, 28, pp. 909-917; Burnie, J., Gilchrist, T., (1983) Ceramic in Surgery, pp. 169-176. , P. Vicenzini. Amsterdam: Elsevier Science Publishers; Ferraz, M.P., Fernandes, M.H., Trigo Cabrai, A., Santos, J.D., Monteiro, F.J., (1999) J Mater Sci Mater Med, 10 (9), pp. 567-576; Oonishi, H., Hench, L.L., Wilson, J., Sugihara, F., Tsuji, E., Kushitani, S., Iwak, H., (1999) J Biomed Mater Res, 44, pp. 31-43; Kitsugi, T., Nakamura, T., Oka, M., Senaha, Y., Got, T., (1996) J Biomed Mater Res, 30, pp. 261-269; Klein, C.P.A.T., Patka, P., Van Der Lubbe, H.B.M., Wolke, J.G.V., De Groot, K., (1991) J Biomed Mater Res, 25, pp. 53-65
Keywords: Bond strength (materials); Bone; Double layer coatings; hydroxyapatite; Implants (surgical); In vivo evaluation; Interfaces (materials); morphology; Phase composition; Phosphates; Plasma sprayed coatings; Rabbit model; Scanning electron microscopy; Sprayed coatings; X ray diffraction analysis

Microstructural characterization and in vitro apatite formation in CaO-P 2O 5-TiO 2-MgO-Na 2O glass-ceramics - Zhang, Y.; Santos, J.D. (Journal of the European Ceramic SocietyJ Eur Ceram Soc, 2001)
Bulk calcium phosphate glass and glass-ceramic with CaO/P 2O 5 molar ratio = 1.25 were prepared through introducing small amounts of Na 2O, MgO, and TiO 2 into the glass. Using XRD analysis, biocompatible β-Ca 2P 2O 7 (β-DCP) and more soluble Ca and Na-containing phases were clearly identified in the microstructure. In vitro bioactivity was assessed by immersion testing in SBF-simulated body fluid and apatite crystals were formed after 4 and 8 weeks of soaking. Porous microstructure was produced through dissolution of soluble phases and desirable porous structure may be achieved by controlling size and distribution of these phases and the leaching process. Therefore, this glass-ceramic is expected to be used as bone repair and regeneration implants and drug delivery carrier.
Cited By (since 1996): 14Export Date: 21 November 2012Source: ScopusCODEN: JECSEdoi: 10.1016/S0955-2219(00)00202-8Language of Original Document: EnglishCorrespondence Address: Zhang, Yong; Inst de Engenharia Biomedica, Porto, PortugalReferences: Hench, L.L., Bioceramics: From concept to clinic (1991) J. Am. Ceram. Soc., 74, pp. 1487-1510;Hench, L.L., Anderson, Ö., (1993) An Introduction to Bioceramics, p. 41. , ed. L. L. Hench and J. Wilson. World Scientific, Singapore; Nakamura, T., Yamamuro, T., Higashi, S., Kokubo, T., Ito, S., A new glass-ceramic for bone replacement: Evaluation of its bonding to bone tissue (1985) J. Biomed. Mater. Res., 19, pp. 685-698; Höland, W., Vogel, W., Nauman, K., Gummel, J., Interface reactions between machinable bioactive glass-ceramics and bone (1985) J. Biomed. Mater. Res., 19, pp. 305-312; Abe, Y., Naruse, A., Hosoe, M., Fukui, H., Hasegawa, J., Development of calcium phosphate glass-ceramics for biomaterials (1975) The 1975 Symposium on Biomaterials, pp. 202-207. , Kyoto; Abe, Y., Calcium phosphate glass-ceramics for biomedical application. . .especially on microporous glass-ceramics (1990) Inter. Forum on Fine Ceramics '90, pp. 78-82. , Nagoya; Kasuga, T., Abe, Y., Novel calcium phosphate ceramics prepared by powder sintering and crystallization of glasses in the pyrophosphate region (1998) J. Mater. Res., 13, pp. 1-4; Kasuga, T., Abe, Y., Calcium phosphate invert glasses with soda and titania (1999) J. Non-Cryst. Solids, 243, pp. 70-74; Hench, L.L., Bioactive ceramics (1988) Bioceramics: Materials Characteristics Versus in Vivo Behavior, pp. 54-71. , ed. P. Ducheyne and J. Lemons. Annals of New York Academy of Sciences, New York; Kokubo, T., Ito, S., Sakka, S., Yamamuro, T., Formation of a high-strength bioactive glass-ceramic in the system MgO-CaO-SiO 2-P 2O 5 (1986) J. Mater. Sci., 21, pp. 536-540; Ohtsuki, C., Kushitani, H., Kokubo, T., Kotani, S., Yamamuro, T., Apatite formation on the surface of Ceravital-type glass-ceramic in the body (1991) J. Biomed. Mater. Res., 25, pp. 1363-1370; Ohtsuki, C., Kokubo, T., Yamamuro, T., Compositional dependence of bioactivity of glasses in the system CaO-SiO 2- Al 2O 3: Its in vitro evaluation (1992) J. Mater. Sci: Mater. in Med., 3, pp. 119-125; Ohtsuki, C., Kokubo, T., Yamamuro, T., Mechanism of apatite formation on CaO-SiO 2-P 2O 5 glasses in a simulated body fluid (1992) J. Non-Cryst. Solids, 143, pp. 84-89; Hosono, H., Zhang, Z., Abe, Y., Porous glass-ceramic in the CaO-TiO 2-P 2O 5 system (1989) J. Am. Ceram. Soc., 72, pp. 1587-1590; Kokubo, T., Ito, S., Huang, Z.T., Hayashi, T., Sakka, S., Ca, P-rich layer formed on high-strength bioactive glass-ceramic A-W (1990) J. Biomed. Mater. Res., 24, pp. 331-343; Kokubo, T., Kushitani, H., Kitsugi, T., Yamamuro, T., Solution able to reproduce in vivo surface-structure changes of bioactive glass-ceramic A-W (1990) J. Biomed. Mater. Res., 24, pp. 721-734; Rey, C., Frèche, M., Heughebaert, M., Heughebaert, J.C., Lacout, J.L., Lebugle, A., Szilagyi, J., Vignoles, M., Apatite chemistry in biomaterial preparation, shaping and biological behavior (1991) Bioceramics, 4, pp. 57-64. , ed. W. Bonfield, G. W. Hastings and K. E. Tanner. Butterworth-Heinemann, London; Vogel, J., Schulze, K.-J., Reif, D., Hartmann, P., Platzbecker, U., Leuner, B., Resorbable porous phosphate invert glasses-first in vitro and in vivo results (1997) Bioceramics, 10, pp. 57-60. , ed. L. Sedel and C. Rey. Elsevier Science; Ohtsuki, C., Kokubo, T., Neo, M., Kotani, S., Yamamuro, T., Nakamura, T., Bando, Y., Bone-bonding mechanism of sintered β-3CaO·P 2O 5 (1991) Phosphorus Res. Bulletin, 1, pp. 191-196; Neo, M., Nakamura, T., Ohtsuki, C., Kokubo, T., Yamamuro, T., Apatite formation on three kinds of bioactive material at an early stage in vivo: A comparative study by transmission electron microscopy (1993) J. Biomed. Mater. Res., 27, pp. 999-1006; Kokubo, T., Kushitani, H., Ohtsuki, C., Sakka, S., Yamamuro, T., Chemical reaction of bioactive glass and glass-ceramics with a simulated body fluid (1992) J. Mater. Sci.: Mater. in Med., 3, pp. 79-83; Blumenthal, N.C., Mechanism of inhibition of calcification (1989) Clin. Orthop. Rel. Res., 247, pp. 279-289
Keywords: Apatite; Bioactivity; Calcium phosphate glass; Ceramic materials; Crystal microstructure; Crystallization; dissociation; glass; Glass ceramics; Leaching; Lime; Magnesia; Phosphorus Compounds; Porous materials; Sodium compounds; Solubility; Titanium dioxide

Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits - Lopes, M.A.; Santos, J.D.; Monteiro, F.J.; Ohtsuki, C.; Osaka, A.; Kaneko, S.; Inoue, H. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 2001)
In vitro and in vivo bioactivity studies were performed to assess the biocompatibility of CaO-P 2O 5 glass-reinforced hydroxyapatite (GR-HA) composites. The ability to form an apatite layer by soaking in simulated body fluid (SBF) was examined and surfaces were characterized using FTIR reflection and thin-film X-ray diffraction analyses. Qualitative histology, histomorphometric measurements, and push-out testing were performed in a rabbit model for characterizing bone/implant bonding. Under the in vitro conditions using SBF, an apatite layer could not be formed on GR-HA composites within 8 weeks. Results of push-out testing showed bonding between the composites and bone, ranging from 130-145 N after 2 weeks of implantation. After the longest implantation period, 16 weeks, the GR-HA composite prepared with the higher content of CaO-P 2O 5 glass showed the highest bonding force, 606 ± 45 N, compared to 459 ± 30 N for sintered HA. Development of immature bone and modifications in the turnover of a more mature bone on the surface of GR-HA composites were similar to those on sintered HA. © 2000 John Wiley & Sons, Inc. In vitro and in vivo bioactivity studies were performed to assess the biocompatibility of CaO-P 2O 5 glass-reinforced hydroxyapatite (GR-HA) composites. The ability to form an apatite layer by soaking in simulated body fluid (SBF) was examined and surfaces were characterized using FTIR reflection and thin-film X-ray diffraction analyses. Qualitative histology, histomorphometric measurements, and push-out testing were performed in a rabbit model for characterizing bone/implant bonding. Under the in vitro conditions using SBF, an apatite layer could not be formed on GR-HA composites within 8 weeks. Results of push-out testing showed bonding between the composites and bone, ranging from 130-145 N after 2 weeks of implantation. After the longest implantation period, 16 weeks, the GR-HA composite prepared with the higher content of CaO-P 2O 5 glass showed the highest bonding force, 606 ± 45 N, compared to 459 ± 30 N for sintered HA. Development of immature bone and modifications in the turnover of a more mature bone on the surface of GR-HA composites were similar to those on sintered HA. © 2000 John Wiley & Sons, Inc.
Cited By (since 1996): 40Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/1097-4636(20010315)54:4<463::AID-JBM10>3.0.CO;2-YPubMed ID: 11426590Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratório de Biomateriais, INEB, Rua do Campo Alegre, 823, 4150-180 Porto, PortugalChemicals/CAS: Bone Substitutes; Composite Resins; Durapatite, 1306-06-5References: Hyakuna, K., Yamamuro, T., Kotoura, Y., Oka, M., Nakamura, T., Kitsugi, T., Kokubo, T., Kushitani, H., Surface reactions of calcium phosphate ceramics to various solutions (1990) J Biomed Mater Res, 24, pp. 471-488;Klein, C.P.A.T., Driessen, A.A., De Groot, K., Van der Hooff, A., Biodegradation behavior of various calcium phosphate materials in bone tissue (1983) J Biomed Mater Res, 17, pp. 769-784; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural Characterization of Glass Reinforced Hydroxyapatite Composites (1994) Biomaterials, 15, pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass Reinforced Hydroxyapatite: A Comprehensive Study of the Effect of Glass Composition on the Crystallography of the Composite (1998) J Biomed Mater Res, 39, pp. 244-251; Lopes, M.A., Santos, J.D., Monteiro, F.J., Glass Reinforced Hydroxyapatite Composites: Secondary Phases Proportions and Densification Effects on Biaxial Bending Strength (1999) J Biomed Mater Res, 48, pp. 734-740; Lopes, M.A., Saramago, B., Santos, J.D., Monteiro, F.J., Hydrophobicity, Surface Tension and Zeta Potential of Glass Reinforced Hydroxyapatite Composites (1999) J Biomed Mater Res, 45, pp. 370-375; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow Cytometry for Assessing Biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Kokubo, T., Ito, S., Huang, Z.T., Hayashi, T., Sakka, S., CaP-rich layer formed on high-strength bioactive glass-ceramic A-W (1990) J Biomed Mater Res, 24, pp. 331-343; Cho, S.B., Nakanishi, K., Kokubo, T., Soga, N., Ohtsuki, C., Nakamura, T., Kitsugi, T., Yamamuro, T., Dependence of Apatite Formation on Silica Gel on Its Structure: Effect of Heat Treatment (1975) J Am Ceram Soc, 78, pp. 1769-1774; Neo, M., Kotani, S., Fujita, Y., Nakamura, T., Yamamuro, T., Bando, Y., Ohtsuki, C., Kokubo, T., Differences in ceramic-bone interface between surface-active ceramics and resorbable ceramics: A study by scanning and transmission electron microscopy (1992) J Biomed Mater Res, 26, pp. 255-267; Hamson, K.R., Toth, J.M., Stiehl, J.B., Lynch, K.L., Preliminary experience with a novel model assessing in vivo mechanical strength of bone grafts and substitute materials (1995) Calcif Tissue Int, 57, pp. 64-68; Hing, K.A., (1996) Assessment of porous hydroxyapatite for bone replacement, , London: University of London; Albrektsson, T., Johansson, C., Quantitative bone tissue reactions to various metallic materials with reference to the so-called osseointegration concept (1991), pp. 357-363. , Davies JE, editor. The bonebiomaterial interface. Toronto: University of Toronto PressProbster, L., Voigh, C.H., Fuhrman, G., Gross, U.M., Tensile and torsional shear strength of the bone implant interface of titanium implants in the rabbit (1994) J Mater Sci: Mater Med, 5, pp. 314-319; Kokubo, T., Kushitani, H., Ebisawa, Y., Kitsugi, T., Kotani, S., Oura, K., Yamamuro, T., Apatite formation on bioactive ceramics in body environment (1989), 1, pp. 157-162. , Oonishi H, Aoki H, Sawai K, editors. Bioceramics. Tokyo: Ishiyaku EuroAmerica, IncLeGeros, R.Z., (1991), pp. 4-45. , Meyers HM, editor. Calcium phosphates in oral biology and medicine. New York: KargerOhtsuki, C., Kokubo, T., Neo, M., Kotani, S., Yamamuro, T., Nakamura, T., Bando, Y., Bone-Bonding Mechanism of Sintered β-3CaO-P 2O 5 (1991) Phosphorus Research Bulletin, 1, pp. 191-196; Kotani, S., Fujita, Y., Kitsugi, T., Nakamura, T., Yamamuro, T., Ohtsuki, C., Kokubo, T., Bone bonding mechanism of β-tricalcium phosphate (1991) J Biomed Mater Res, 25, pp. 1303-1315; Lu, J.X., Gallur, A., Flautre, B., Anselme, K., Descamps, M., Thierry, B., Hardouin, P., Comparative study of tissue reactions to calcium phosphate ceramics among cancellous, cortical, and medullar bone site in rabbits (1998) J Biomed Mater Res, 42, pp. 357-367; Kitsugi, T., Nakamura, T., Oka, M., Senaha, Y., Goto, T., Bonebonding behavior of plasma-sprayed coatings of bioglass, AW-glass ceramic, and tricalcium phosphate on titanium alloy (1996) J Biomed Mater Res, 30, pp. 261-269; Kitsugi, T., Yamamuro, T., Nakamura, T., Kotani, S., Kokubo, T., Takeuchi, H., Four calcium phosphate ceramics as bone substitutes for non-weight-bearing (1993) Biomaterials, 14, pp. 216-224; De Lauge, G.L., De Putter, C., De Wijs, F.L.J.A., Histological and ultrastructural appearance of the hydroxy apatite-bone interface (1990) J Biomed Mater Res, 24, pp. 829-845; Yamada, S., Nakamura, T., Kokubo, T., Oka, M., Yamamuro, T., Degradation of the apatite layer formed on bioactive ceramics and the underlying ceramic surface by osteoclasts in a culture system (1994) Cells and Materials, 4, pp. 347-356; Brunski, J.B., Influence of biomechanical factors at the bone-biomaterial interface (1990), pp. 391-405. , Davies JE, editor. The bone-biomaterial interface. Toronto: University of Toronto PressDhert, J.A., Thomsen, P., Blomgren, A.K., Esposito, M., Ericson, L.E., Verbout, A.J., Integration of press-fit implants in cortical bone: A study on interface kInetics (1998) J Biomed Mater Res, 41, pp. 574-583; Gao, T.J., Lindholm, T.S., Kommonen, B., Ragni, P., Paronzini, A., Lindholm, T.C., Microscopic evaluation of bone-implant contact beween HA, bioactive glass and tricalcium phosphate implanted in sheep diaphyseal defects (1995) Biomaterials, 16, pp. 1175-1179; Oonishi, H., Hench, L.L., Wilson, J., Sugihara, F., Tsuji, E., Kushitani, S., Iwaki, H., Comparative bone growth behavior in granules of bioceramic materials of various sizes (1999) J Biomed Mater Res, 44, pp. 31-43; Marie, P.J., De Vernejoul, M.C., Lomri, A., Stimulation of bone formation in osteoporosis patients treated with fluoride associated with increased DNA synthesis by osteoblast cells in vitro (1992) J Bone Miner Res, 7, pp. 103-113; Rodan, G.A., Introduction to bone biology (1992) Bone, 13, pp. S3-S6
Keywords: animal experiment; animal tissue; Animals; article; Biocompatibility; Body fluids; Bonding; Bone; Bone Substitutes; bone turnover; Ceramic materials; Composite Resins; Durapatite; Fiber reinforced materials; Fourier transform infrared spectroscopy; glass; Glass reinforced hydroxyapatite composites; Glass-reinforced hydroxyapatite composites; Histological studies; histology; Histomorphometric measurements; hydroxyapatite; implant; implantation; Implants (surgical); In vitro bioactivity; In vivo evaluation; Interfaces (materials); male; nonhuman; orthopedic equipment; ossification; Prosthesis Implantation; Push out testing; Push-out testing; rabbit; Rabbits; Spectroscopy, Fourier Transform Infrared; Stress, Mechanical; Surgical equipment; tibia; Time Factors; X ray diffraction; X ray diffraction analysis

Silicon nitride - bioglass composite for biomedical applications - Santos, J.D.; Amaral, M.; Oliveira, S.M.; Lopes, M.A.; Silva, R.F. (Key Engineering MaterialsKey Eng Mat, 2001)
This study aimed at preparing novel highly toughened bioactive ceramic composite composed of Si 3N 4 matrix and Bioglass using a hot pressing technique. Densification rate, hardness and fracture toughness of this novel composite were assessed as well as in vitro bioactivity using a simulated body fluid (SBF). A fracture toughness of 5.2±0.3 MPa.m. 1/2 was achieved for fully densified samples, which complies with K 1c value reported for cortical bone. This novel composite, which can be used in high load medical applications, seems to overcome the drawback of low fracture toughness presented by most currently available bioactive ceramics.
Conference code: 57760Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; Universidade do Porto, Porto, PortugalReferences: Hench, L.L., Wilson, J., (1993) An Introduction to Bioceramics;(1995) Engineering Materials Handbook, Ceramics and Glasses, Asm International, 4, pp. 812-820; Fishman, G., Clare, A., Hench, L.L., (1995) Materials and Applications, 48; Niihara, K., Morena, R., Hasselman, D.P., (1982) J. Mater. Sci., 1, pp. 13-16; Hench, L.L., (1998) Bioceramics, J. Am. Ceram. Soc., 81 (7), pp. 1705-1728; Landis, W.J., Martin, J.R., (1984) J. Vac. Sci. Technol., A2, p. 1108
Keywords: Bioactive ceramic composite; Bioglass; Biomaterials; Body fluids; Bone; Ceramic matrix composites; cortical bone; Densification; Fracture toughness; Glass ceramics; Hot pressing; Medical applications; Silicon nitride; Simulated body fluid

Starch based copolymers as biomaterials in vivo biocompatibility study - Souillac, V.; Fricain, J.C.; Bareille, R.; Reis, R.L.; Chauveaux, D.; Baquey, C. (Key Engineering MaterialsKey Eng Mat, 2001)
This report is a preliminary study of a starch-based copolymer that was used as a bone substitute. The interest of this study was to evaluate the possibility of using a hydrophilic material as a bone substitute. We studied this copolymer alone, after phosphorylation, and after hydroxyapatite coating.
Conference code: 57760Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Souillac, V.; Universite Bordeaux 2, Bordeaux, FranceReferences: Hollinger, J.O., Brekke, J., Gruskin, E., Lee, D., (1996) Clin. Orthop., 324, p. 55;Nizard, R., Bizot, P., Sedel, L., (1996) Encycl. Med. Chir., Orthopédie-traumatologie, 44 (3). , 20p; Delécrin, J., Dupraz, A., Passuti, N., (1996) Cahiers D'enseignement de la SOFCOT, 57, p. 97; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) J. Polym. Adv. Technol., 7, p. 784; Kokubo, T., Hata, K., Nakamura, T., Yamamuro, T., (1991) Bioceramics, 4, p. 113. , UK; Reis, R.L., Cunha, A.M., Fernandes, M.H., (1997) J. Mater. Sci. : Mater, in Medecine, 8, p. 897; Vilamitjana-Amedee, J., Bareille, R., Rouais, F., Harmand, M.F., (1993) In Vitro Cell Dev. Biol., 29, p. 699; Parish, C.R., Mullbacher, A., (1983) J. Immunol. Meth., 58, p. 225; Mosmann, T., (1983) J. Immunol. Meth., 65, p. 55; Koshino, T., Kubota, W., Morii, T., (1995) Biomaterials, 16, p. 125; Pasquier, G., Flautre, B., Blary, M.C., Anselme, K., Hardouin, P., (1996) Journal of Materials Science, 7, p. 683; Nagano, M., Kitsugi, T., Nakamura, T., Kokubo, T., Tanahashi, M., (1996) J. Biomed. Mater. Res., 31, p. 487; Miyamoto, T., Takahashi, S., Ito, H., Inagaki, H., (1989) J. Biomed. Mater. Res., 23, p. 125
Keywords: Biocompatibility; Bone; Bone substitute; Copolymers; Ethanol; Ethylene; hydroxyapatite; Hydroxyapatite coating; Implants (surgical); orthopedics; Phosphates; phosphoric acid; Phosphorylation; Starch; Substitution reactions; Vinyl resins

Crystallization and microstructure analysis of calcium phosphate-based glass ceramics for biomedical applications - Zhang, Y.; Santos, J.D. (Journal of Non-Crystalline SolidsJ Non Cryst Solids, 2000)
Calcium phosphate glasses and glass ceramics (CaO/P 2O 5 = 1.25 in molar ratio) modified by small amounts of additives such as Na 2O, MgO, TiO 2 and ZrO 2 were prepared after appropriate heat treatment for nucleation and crystallization. Based upon differential thermal analysis (DTA) results, a two-step heat treatment was used for crystal nucleation and growth. X-ray diffraction (XRD) analysis demonstrated that bioresorbable β-Ca 2P 2O 7 (β-DCP), β-Na 2CaP 2O 7, Na 2Mg(PO 3) 4 phases were formed in the glass matrix depending upon the relative contents of the additives. By adding higher contents of Na 2O and TiO 2 and using CaO/P 2O 5 = 1.5-2.0, crystallization of β-DCP and Ca 3(PO 4) 2 (β-TCP), and the formation of a dense structure in the glass ceramics were obtained. The precipitation of these crystals could be well distinguished at a magnification of 4000× and phases were dispersed in areas of micron size. A porous structure may be easily formed after the soluble phases are dissolved in physiological media. These glass ceramics with high CaO/P 2O 5 ratio, modified by the above mentioned additives are expected to find use as implants for bone replacement/regeneration and drug delivery carriers synergistically, because the soluble phases may act as drug delivery carriers and the porous structure will allow for bone ingrowth.
Cited By (since 1996): 42Export Date: 21 November 2012Source: ScopusCODEN: JNCSBdoi: 10.1016/S0022-3093(00)00115-0Language of Original Document: EnglishCorrespondence Address: Zhang, Yong; Inst de Engenharia Biomedica, Porto, PortugalReferences: Kitsugi, T., Yamamuro, T., Nakamura, T., Kotani, S., Kokubo, T., Takeuchi, H., (1993) Biomaterials, 14, p. 216;Kitsugi, T., Yamamuro, T., Nakamura, T., Oka, M., (1995) Biomaterials, 16, p. 1101; Doremus, R.H., (1992) J. Mater. Sci., 27, p. 285; Kokubo, T., (1993) An Introduction to Bioceramics, p. 75. , in L.L. Hench Wilson J. (Eds.), World Scientific, Singapore; Tracy, B., Doremus, R.H., (1984) J. Biomed. Mater. Res., 18, p. 719; Jha, L.J., Best, S.M., Santos, J.D., Bonfield, W., (1997) J. Mater. Sci.: Mater. Med., 8, p. 185; Hench, L.L., (1991) J. Am. Ceram. Soc., 74, p. 1487; Hench, L.L., Anderson, Ö., (1993) An Introduction to Bioceramics, p. 41. , in: L.L. Hench, J. Wilson (Eds.), World Scientific, Singapore; Nakamura, T., Yamamuro, T., Higashi, S., Kokubo, T., Ito, S., (1985) J. Biomed. Mater. Res., 19, p. 685; Höland, W., Vogel, W., Nauman, K., Gummel, J., (1985) J. Biomed. Mater. Res., 19, p. 303; Kasuga, T., Abe, Y., (1998) J. Mater. Res., 13, p. 1; Rawson, H., (1960) Inorganic Glass-Forming System, p. 155. , Academic, London; Abe, Y., Naruse, A., Hosoe, M., Fukui, H., Hasegawa, J., (1975) In: The 1975 Symposium on Biomaterials, p. 202. , Kyoto; Abe, Y., (1990) In: International Forum on Fine Ceramics '90, p. 78. , Nagoya; Kasuga, T., Abe, Y., (1999) J. Non-Cryst. Solids, 243, p. 70; Hosono, H., Zhang, Z., Abe, Y., (1989) J. Am. Ceram. Soc., 72, p. 1587; Posner, A.S., (1969) Phys. Rev., 49, p. 760; Kitsugi, T., Yamamuro, T., Nakamura, T., Kotani, S., Kokubo, T., Takeuchi, H., (1993) Biomaterials, 14, p. 216; Klein, C.P., De Blieck-Hogervorst, J.M., Wolke, J.G., De Groot, K., (1990) Biomaterials, 11, p. 509; Kitsugi, T., Yamamuro, T., Nakamura, T., Oka, M., (1995) Biomaterials, 16, p. 1101; Müller-Mai, C., Berger, G., Voigt, C., Bakki, B., Gross, U., (1997) Bioceramics, 10, p. 53. , in: L. Sedel, C. Rey (Eds.), Elsevier, Amsterdam; Vogel, J., Schulze, K.-J., Reif, D., Hartmann, P., Platzbecker, U., Leuner, B., (1997) Bioceramics, 10, p. 57. , in: L. Sedel, C. Rey (Eds.), Elsevier, Amsterdam; Gil, F.J., Terradas, R., Clement, J., Avila, G., Martinez, S., Planell, J.A., (1997) Bioceramics, 10, p. 553. , in: L. Sedel, C. Rey (Eds.), Elsevier, Amsterdam; Sun, K.-H., (1947) J. Am. Ceram. Soc., 30, p. 277; Arm, D.M., Tencer, A.F., Brain, S.D., Celino, D., (1996) Biomaterials, 17, p. 703; Denissen, D., Van Beck, E., Lowick, C., Papapoulos, S., Van Den Hoof, A., (1993) Bone Miner., 25, p. 123; Nguyen, T.H., Cromwell, M., Wonc, R., Beck, L.S., Plouhar, P., Onpipattatanskul, B., (1994) Proceedings of the International Symposium Control. Rel. Bioact. Mater., 21, p. 122; Uchida, A., Shinto, Y., Araki, N., Ono, K., (1992) J. Orthop. Res., 10, p. 440
Keywords: Additives; Biomaterials; Calcium Compounds; calcium phosphate; Ceramic materials; Crystal microstructure; Crystallization; Differential thermal analysis; glass; Glass ceramics; Nucleation; Phosphates; Porous materials; Precipitation (chemical); Sodium dioxide; X ray crystallography

Direct and indirect effects of P 2O 5 glass reinforced-hydroxyapatite composites on the growth and function of osteoblast-like cells - Lopes, M.A.; Knowles, J.C.; Santos, J.D.; Monteiro, F.J.; Olsen, I. (BiomaterialsBiomaterials, 2000)
Human osteoblast-like cells were plated on hydroxyapatite and P 2O 5-glass reinforced hydroxyapatite composite discs. They were also cultured in the presence of media obtained by incubating the discs in the absence of cells. The effects of these direct and indirect interactions were examined by measuring cell proliferation and the expression of certain key extracellular matrix antigens. One composite was found to initially delay cell growth, while the extract of a different composite appeared to down-regulate DNA synthesis. Flow cytometry analysis showed that growth directly on the discs had little effect on collagen type I, but reduced fibronectin and osteocalcin levels. The extracts of the materials generally had less effect, although one extract obtained from the glass-reinforced hydroxyapatite significantly down-regulated fibronectin. These in vitro studies thus suggest that there were only few differences overall in the growth of the cells directly on the glass-reinforced compared with the hydroxyapatite discs and also only relatively small effects of the extracts on the cells. However, the flow cytometry results suggest that both the materials and the extracts may have a potentially important influence on connective tissue production, and that these effects are both material- and antigen-specific. Copyright (C) 2000 Elsevier Science Ltd. Human osteoblast-like cells were plated on hydroxyapatite and P 2O 5-glass reinforced hydroxyapatite composite discs. They were also cultured in the presence of media obtained by incubating the discs in the absence of cells. The effects of these direct and indirect interactions were examined by measuring cell proliferation and the expression of certain key extracellular matrix antigens. One composite was found to initially delay cell growth, while the extract of a different composite appeared to down-regulate DNA synthesis. Flow cytometry analysis showed that growth directly on the discs had little effect on collagen type I, but reduced fibronectin and osteocalcin levels. The extracts of the materials generally had less effect, although one extract obtained from the glass-reinforced hydroxyapatite significantly down-regulated fibronectin. These in vitro studies thus suggest that there were only few differences overall in the growth of the cells directly on the glass-reinforced compared with the hydroxyapatite discs and also only relatively small effects of the extracts on the cells. However, the flow cytometry results suggest that both the materials and the extracts may have a potentially important influence on connective tissue production, and that these effects are both material- and antigen-specific.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(00)00007-7PubMed ID: 10817269Language of Original Document: EnglishCorrespondence Address: Olsen, I.; Department of Periodontology, Eastman Dental Institute, University College London, 256 Gray's Inn Road, London WC1X 8LD, United Kingdom; email: iolsen@eastman.ucl.ac.ukChemicals/CAS: Antigens; Biocompatible Materials; DNA, 9007-49-2; Hydroxyapatites; PhosphatesReferences: Kirkpatrick, C.J., A critical view of current and proposed methodologies for biocompatibility testing: Cytoxicity in vitro (1992) Regulatory Affairs, 4, pp. 13-32;Hanson, S., Lalor, P.A., Niemi, S.M., Ratner, B.D., (1996) Biomaterials Science. An Introduction to Materials in Medicine, pp. 215-242. , B.D. Ratner, & A.S. Hoffman. Basel: Karger; Bou-Gharios, G., Osman, J., Atherton, A., Monoghan, P., Vancheeswaran, R., Black, C., Olsen, I., Expression of ectopeptidaes in scleroderma (1995) Ann Rheum Dis, 54, pp. 111-116; Goseki, T., Shimizu, N., Iwasawa, T., Takiguchi, H., Abiko, Y., Effects of in vitro cellular aging on alkaline phosphatase, cathepsin activities and collagen secretion of human periodontal ligament-derived cells (1996) Mech Age Dev, 91, pp. 1761-1783; Parkar, M.H., Kuru, L., O'Hare, M., Newman, H.N., Hughes, F., Olsen, I., Retroviral transduction of periodontal cells with a temperature-sensitive SV40 large T antigen (1999) Archs Oral Biol, 44, pp. 823-834; Simon, L.V., Beauchamp, J.R., O'Hare, M., Olsen, I., Establishment of long-term myogenic cultures from patients with Duchenne muscular dystrophy by retroviral transduction of a temperature-sensitive SV40 large T-antigen construct (1996) Exp Cell Res, 224, pp. 264-271; Clover, J., Gowen, M., Are MG-63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype (1994) Bone, 15, pp. 585-591; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Di Silvio, L., A novel application of two biomaterial for the delivery of growth hormone and its effect on osteoblasts (1995) PhD Thesis, , Univ Lon: Univ Coll Lon Med Sch; Kapuscinski, J., Skoczylas, B., Simple and rapid fluorimetric method for DNA microassay (1977) Anal Biochem, 83, pp. 252-257; Nishizawa, K., Toriyama, M., Suzuki, T., Kawamoto, Y., Yokogawa, Y., Nagae, H., Effects of the surface wettability and zeta potential of bioceramics on the adhesiveness of anchorage-dependent animal cells (1993) J Ferm Bioengng, 75, pp. 435-437; Chesmel, K.D., Clark, C.C., Brighton, C.T., Black, J., Cellular response to chemical and morphologic aspects of biomaterial surfaces. II. The biosynthetic and migratory response of bone cell populations (1995) J Biomed Mater Res, 29, pp. 1101-1110; Harmand, M.F., Human cell culture and characterization of cell-biomaterial interface (1992) Clinical Materials, 11, pp. 145-150; Lincks, J., Boyan, B.D., Blanchard, C.R., Lohmann, C.H., Liu, Y., Cochran, D.L., Dean, D.D., Schawrtz, Z., Response of MG63 osteoblast-like cells to titanium and titanium alloy is dependent on surface roughness and composition (1998) Biomaterials, 19, pp. 2219-2232; Lopes, M.A., Santos, J.D., Monteiro, F.J., Glass reinforced hydroxyapatite composites: Secondary phases proportions and densification effects on biaxial bending strength (1999) J Biomed Mater Res, 48, pp. 734-740; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Lopes, M.A., Saramago, B., Santos, J.D., Monteiro, F.J., Hydrophobicity and zeta potencial of glass reinforced hydroxyapatite composites (1999) J Biomed Mater Res: Appl Biomater, 45, pp. 370-375; Hall, B.K., (1992) Fracture Repair and Regeneration, pp. 33-66. , Boca Raton, FL, USA: CRC Press; Legeros, R.Z., (1991) Calcium Phosphates in Oral Biology and Medicine, , Basel: Karger; Altankov, G., Groth, T., Fibronectin matrix formation and the biocompatibility of materials (1996) J Mater Sci: Mater Med, 7, pp. 425-429; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Lopes, M.A., Knowles, J.C., Hing, K., Santos, J.D., Monteiro, F.J., Olsen, I., Sedel, L., Rey, C., Biological evaluation of glass reinforced hydroxyapatite by flow cytometry (1997) Bioceramics, 10, pp. 575-578. , Paris, Oxford, UK: Elsevier; Kirkpatrick, C.J., Mittermayer, C., Theoretical and practical aspects of testing potential biomaterials in vitro (1990) J Mater Sci: Mater Med, 1, pp. 9-13; Marie, P.J., De Vernejoul, M.C., Lomri, A., Stimulation of bone formation in osteoporosis patients treated with fluoride associated with increased DNA synthesis by osteoblastic cells in vitro (1992) J Bone Miner Res, 7, pp. 103-113; Davies, J.E., In vitro modelling of the bone-implant interface (1996) Anat Rec, 245, pp. 426-445; Verrier, S., Bareille, R., Rovira, A., Dard, M., Amdee, J., Human osteoprogenitor responses to orthopaedic implant: Mechanism of cell attachment and cell adhesion (1996) J Mater Sci: Mater Med, 17, pp. 46-51; Sumner, H., Abraham, D., Bou-Gharios, G., Plater-Zyberk, C., Olsen, I., Simultaneous measurement of cell surface and intracellular antigens by multiple flow cytometry (1991) J Immun Meth, 136, pp. 259-267; Bou-Gharios, G., Osman, J., Black, C., Olsen, I., Excess matrix accumulation in Scleroderma is caused partly by differential regulation of stromelysin and TIMP-1 synthesis (1994) Clin Chim Acta, 231, pp. 69-78; Kuru, L., Parkar, M.H., Griffiths, G.S., Newman, H.N., Olsen, I., Flow cytometry analysis of functionally distinct gingival and periodontal ligament cells (1998) J Dent Res, 77, pp. 555-564; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of glass on the biocompatibility of plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings (1999) J Biomed Mater Res, 47, pp. 603-611
Keywords: Animal cell culture; antigen expression; Antigens; article; Biocompatibility; Biocompatible Materials; Biomaterials; Bone; Bone cells; cell antigen; Cell culture; Cell Division; cell function; cell growth; Cell Line; cell proliferation; cell structure; collagen type 1; controlled study; DNA; DNA Replication; DNA synthesis; extracellular matrix; Fibronectin; flow cytometry; glass; Glass fibers; Glass-reinforced hydroxyapatite; Growth kinetics; human; human cell; Humans; hydroxyapatite; Hydroxyapatites; immunofluorescence; In vitro; Microscopy, Electron, Scanning; osteoblast; Osteoblasts; osteocalcin; Phosphate minerals; Phosphates; phosphorus pentoxide; priority journal; Proteins; Reinforcement; Scanning electron microscopy

Flow cytometry analysis of the effects of pre-immersion on the biocompatibility of glass-reinforced hydroxyapatite plasma-sprayed coatings - Ferraz, M.P.; Knowles, J.C.; Olsen, I.; Monteiro, F.J.; Santos, J.D. (BiomaterialsBiomaterials, 2000)
Multilayered coatings composed of mixtures of HA and P 2O 5-based bioactive glasses are of potential clinical benefit in orthopaedic and dental surgery. Pre-immersion of these materials has been reported to further enhance their efficacy in vivo, although the precise biological effects of this treatment are not yet known. In this study we have therefore prepared double-layer plasma-sprayed coatings and evaluated the effects of pre-immersion on the growth and function of human osteosarcoma cells in vitro, using the MTT assay and flow cytometry analysis, respectively. The results showed that the increase in numbers of viable cells was the same or elevated following incubation on the pre-immersed HA and glass-reinforced HA coatings compared with the non-immersed materials. In addition, the expression of bone sialoprotein and fibronectin, two key connective tissue antigens, was up-regulated in cultures grown on the pre-immersed surfaces compared with the non-treated materials. Moreover, cell numbers and antigen expression both improved as the proportion of glass increased, particularly in the pre-immersed samples. Our findings thus suggest that the immersion treatment of these materials appeared to improve the response of these bone-like cells. Copyright (C) 2000 Elsevier Science Ltd. Multilayered coatings composed of mixtures of HA and P 2O 5-based bioactive glasses are of potential clinical benefit in orthopaedic and dental surgery. Pre-immersion of these materials has been reported to further enhance their efficacy in vivo, although the precise biological effects of this treatment are not yet known. In this study we have therefore prepared double-layer plasma-sprayed coatings and evaluated the effects of pre-immersion on the growth and function of human osteosarcoma cells in vitro, using the MTT assay and flow cytometry analysis, respectively. The results showed that the increase in numbers of viable cells was the same or elevated following incubation on the pre-immersed HA and glass-reinforced HA coatings compared with the non-immersed materials. In addition, the expression of bone sialoprotein and fibronectin, two key connective tissue antigens, was up-regulated in cultures grown on the pre-immersed surfaces compared with the non-treated materials. Moreover, cell numbers and antigen expression both improved as the proportion of glass increased, particularly in the pre-immersed samples. Our findings thus suggest that the immersion treatment of these materials appeared to improve the response of these bone-like cells.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(99)00249-5PubMed ID: 10721750Language of Original Document: EnglishCorrespondence Address: Olsen, I.; Department of Periodontology, Eastman Dental Institute, University College London, 256 Gray's Inn Road, London WC1X 8LD, United Kingdom; email: iolsen@eastman.ucl.ac.ukChemicals/CAS: Biocompatible Materials; bone sialoprotein; Coated Materials, Biocompatible; Durapatite, 1306-06-5; Fibronectins; SialoglycoproteinsManufacturers: Plasma Biotal, United KingdomReferences: Passuti, N., Daculsi, G., Martin, S., Macroporous calcium phosphate ceramics for long bone surgery in human and dogs - Clinical and histological studies (1990) Clinical Implant Materials, pp. 255-258. , V. Soltesz, & A. Lee. Amsterdam: Elsevier Science Publishers;Legeros, R., Calcium phosphate materials in restorative dentistry (1988) A Review. Adv Dent Res, 2, pp. 164-180; Hench, L.L., Bioactive ceramics: From concept to clinic (1992) J Am Ceram Soc, 74, pp. 1487-1510; Conish, H., Aoki, H., Sawai, K., (1981) Science and Medical Applications of Hydroxyaptite, , editors Tokyo: Takyama Press System Centre Co; Raemdonck, W., Ducheyne, P., Meester, P., Calcium phosphate ceramics (1984) Metal and Ceramic Materials, pp. 143-166. , P. Ducheyne, & G.W. Hastings. Boca Raton, FL, USA: CRC Press; Rey, C., Freche, M., Heughebaert, M., Vignoles, M., Apatite chemistry in biomaterial preparation, shaping and biological behaviour (1991) Fourth Symposium on Ceramics in Medicine - Bioceramics 4, pp. 57-64. , G.W. Hastings, & K.E. Tanner. London: Butterworth-Heinemann; Nagase, M., Abe, Y., Udagwa, E., Toxicity of silica-containing calcium phosphate glasses demonstrated in mice (1992) Biomaterials, 13, pp. 172-175; Burnie, J., Gilchrist, T., Controlled released glass - A new biomaterial (1983) Ceramics in Surgery, pp. 169-176. , P. Vicenzini. Amsterdam: Elsevier Science Publishers; Burnie, F., Gilchrist, T., (1983) Ceramics in Surgery, pp. 177-180. , P. Vicenzini. Amsterdam: Elsevier Science; Rawlings, R.D., Rogers, P.S., Stokes, P.M., Glass-ceramics containing apatite (1987) High Tech Ceramics, pp. 73-82. , P. Vicenzini. Amsterdam: Elsevier Science Publishers; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterization of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Santos, J.D., Lakhan, J.J., Monteiro, F.J., Surface modifications of glass-reinforced hydroxyapatite composites (1995) Biomaterials, 16, pp. 521-526; Ferraz, M.P., Monteiro, F.J., Santos, J.D., In vitro bioactivity and osteocompatibility evaluation of plasma sprayed hydroxyapatite/glass composite coatings onto Ti-6Al-4V substrates (1997) Ninth International Conference on Biomedical Engineering, pp. 557-559. , In: Goh JCH, editor Singapore; Klein, C.P.A.T., Patka, P., Van Der Lubbe, H.B.M., Plasma-sprayed coatings of tetracalciumphosphate, hydroxyl-apatite, and α-TCP on titanium alloy: An interface study (1991) J Biomed Mater Res, 25, pp. 53-65; Jansen, J.A., Van Der Waerden, J.P., Wolke, J.G., Histologic investigation of the biologic behavior of different hydroxyapatite plasma-sprayed coatings in rabbits (1993) J Biomed Mater Res, 4, pp. 603-610; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., The ultrastructure of the bone-hydroxyapatite interface in vitro (1992) J Biomed Mater Res, 26, pp. 1365-1382; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., Comparative biological properties of HA plasma-sprayed coatings having different crystallinities (1994) J Mater Sci: Mater Med, 5, pp. 11-17; Lugscheider, E., Knepper, M., Heimberg, B., Dekker, A., Kirkpatrick, C.J., Cytotoxicity investigations of plasma-sprayed calcium-phosphate coatings (1994) J Mater Sci: Mater Med, 5, pp. 371-375; Courteney-Harris, R.G., Kayser, M.V., Downes, S., Comparison of the early production of extracellular matrix on dense hydroxyapatite and hydroxyapatite-coated titanium in cell and organ culture (1995) Biomaterials, 16, pp. 489-495; Labat, B., Chanson, A., Frey, J., Effects of γ-alumina and hydroxyapatite coatings on the growth and metabolism of human osteoblasts (1995) J Biomed Mater Res, 29, pp. 1397-1401; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., Adult human bone cells derived from jaw bones cultured on plasma-sprayed or polished surfaces to titanium or hydroxyapatite discs (1996) J Mater Sci: Mater Med, 7, pp. 21-28; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Ariola, C.R., Granchi, D., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin Mater, 15, pp. 173-190; Puleo, D.A., Preston, K.E., Shaffer, J.B., Bizios, R., Examination of osteoblast-orthopaedic biomaterial interactions using molecular techniques (1993) Biomaterials, 14, pp. 111-114; Clifford, C.J., Downes, S., A comparative study of the use of colorimetric assays in the assessment of biocompatibility (1996) J Mater Sci: Mater Med, 7, pp. 637-643; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P 2O 5 glass hydroxyapatite double layer plasma sprayed coatings: In vitro evaluation (1999) J Biomed Mater Res, 45, pp. 376-383; Ferraz, M.P., Fernandes, M.H., Trigo Cabral, A., Santos, J.D., Monteiro, F.J., In vitro growth and differentiation of osteoblast-like human bone marrow cells on glass reinforced HA plasma sprayed coatings (1999) J Mater Sci: Mater Med, 10, pp. 567-576; Macey, M.G., (1994) Flow Cytometry - Clinical Applications, , editor Oxford: Blackwell Scientific; Shapiro, H.M., (1995) Practical Flow Cytometry, , New York: Wiley-Liss; Melamed, M.R., Lindmo, T., Mandelsohn, M.L., (1990) Flow Cytometry and Sorting, , editors New York: Wiley-Liss; Muirhead, K.A., Horan, P.K., Applications of flow cytometry to tissue culture systems (1983) Adv Cell Culture, 3, pp. 57-91; Corver, W.E., Cornelisse, C.J., Fleuren, G.J., Simultaneous measurement of two cellular antigens and DNA using fluorescein-isothiocyanate, R-phycoerythrin and propidium iodide on a standard FACScan (1994) Cytometry, 15, pp. 117-128; Pande, G., Kumar, N.A., Manogaran, P.S., Flow cytometric study of changes in intracellular free calcium during the cell cycle (1996) Cytometry, 24, pp. 55-63; Kamiya, I., Okuda, K., Hara, K., Flow cytometric identification and detection of Porphyromonas gingivalis by a LPS specific monoclonal antibody (1994) J Periodont, 65, pp. 309-315; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of glass on the biocompatibility of plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings J Biomed Mater Res, , in press; Cowles, E.A., DeRome, M.E., Pastizzo, G., Brailey, L.L., Gronowicz, G.A., Mineralization and the expression of matrix proteins during in vivo bone development (1998) Calcif Tissue Int, 62, pp. 74-82; Globus, R.K., Dotty, S.B., Lull, J.C., Holmuhamedov, E., Humphries, M.J., Damsky, C.H., Fibronectin is a survival factor for differentiated osteoblasts (1998) J Cell Sci, 111, pp. 1385-1393; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Wojciech, G., Melamed, M.R., Darzynkiewicz, Z., Analysis of apoptosis by flow cytometry (1998) Flow Cytometry Protocols, pp. 217-238. , M.J. Jaroszeski, & R. Heller. Totowa, NJ, USA: Humana Press
Keywords: antigen expression; article; Bioactive glasses; Biocompatibility; Biocompatible Materials; Biomaterials; Cell culture; Cell Division; cell growth; cell proliferation; Cell size; Coated Materials, Biocompatible; controlled study; cytology; Cytoplasmic Granules; Dental Materials; drug manufacture; Durapatite; Fibronectin; Fibronectins; flow cytometry; Flow cytometry analysis; glass; Glass fibers; Glass-reinforced hydroxyapatite; Growth kinetics; human; human cell; Humans; hydroxyapatite; in vitro study; materials testing; orthopedics; Osteosarcoma; osteosarcoma cell; Phosphates; Plasma spraying; Pre-immersion; priority journal; protein expression; Proteins; Sialoglycoproteins; sialoprotein; Sprayed coatings; Surface Properties; technique; Tumor Cells, Cultured

Microstructural dependence of Young's and shear moduli of P 2O 5 glass reinforced hydroxyapatite for biomedical applications - Lopes, M.A.; Silva, R.F.; Monteiro, F.J.; Santos, J.D. (BiomaterialsBiomaterials, 2000)
P 2O 5 glass reinforced hydroxyapatite composite materials were prepared through a liquid-phase sintering process. Secondary phases, β- and α- tricalcium phosphate (β-TCP and α-TCP), were formed in the microstructure of the composites, due to the reaction between the liquid glassy phase and the hydroxyapatite matrix. The dynamic Young's modulus (E) and shear modulus (G) of these composites were determined using an impulse excitation method. By applying the Duckworth-Knudsen equation, the elastic property results were correlated with the relative proportion of β-TCP and α-TCP phases and with the porosity percentage present in the microstructure. Glass reinforced hydroxyapatite composites showed lower Young's and shear moduli than unmodified hydroxyapatite, mainly due to presence of β-TCP phase. The Duckworth-Knudsen model demonstrated an exponential dependence of E and G modulus with porosity and mathematical equations were derived for composite materials with porosity correction factors (b) of 4.04 and 4.11, respectively, indicating that porosity largely decreased both E and G moduli. (C) 2000 Elsevier Science Ltd. 2O 5 glass reinforced hydroxyapatite composite materials were prepared through a liquid-phase sintering process. Secondary phases, β- and α-tricalcium phosphates (β-TCP and α-TCP), were formed in the microstructure of the composites, due to the reaction between the liquid glassy phase and the hydroxyapatite matrix. The dynamic Young's modulus (E) and shear modulus (G) of these composites were determined using an impulse excitation method. By applying the Duckworth-Knudsen equation, the elastic property results were correlated with the relative proportion of β-TCP and α-TCP phases and with the porosity percentage present in the microstructure. Glass reinforced hydroxyapatite composites showed lower Young's and shear moduli than unmodified hydroxyapatite, mainly due to the presence of β-TCP phase. The Duckworth-Knudsen model demonstrated an exponential dependence of E and G modulus with porosity and mathematical equations were derived for composite materials with porosity correction factors (b) of 4.04 and 4.11, respectively, indicating that porosity largely decreased both E and G moduli.
Cited By (since 1996): 32Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(99)00248-3PubMed ID: 10711972Language of Original Document: EnglishCorrespondence Address: Lopes, M.A.; INEB Inst. de Engenharia Biomedica, Laboratorio de Biomaterials, Rua do Campo Alegre 823, 4150 Porto, PortugalChemicals/CAS: Biocompatible Materials; Hydroxyapatites; PhosphatesReferences: Burstein, A., Wright, T.M., (1994) Fundamentals of Orthopaedic Biomechanics, , Lippincott: Williams & Wilkins;Carter, D.R., Giori, N.J., Effect of mechanical stresses on tissue differentiation in the bony implant bed (1991) In the Bone-material Interface, pp. 367-379. , J.E. Davies. Toronto: University of Toronto Press; (1995) E - Advanced Technical Ceramics, (PART 2). , European prestandard, ref. no. ENV 843-2:; Schreiber, E., Anderson, O.L., Soga, N., (1989) Elastic Constant and Their Measurements, , New York: McGraw-Hill; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Knowles, J.C., Talal, S., Santos, J.D., Sintering effects in a glass reinforced hydroxyapatite (1996) Biomaterials, 17, pp. 1437-1442; Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Biological evaluation of glass reinforced hydroxyapatite by flow cytometry (1998) Bioceramics, 10, pp. 575-578; Rice, R.W., Microstructure dependence of mechanical behaviour (1977) Treatise on Materials Science and Technology, 11, pp. 200-382. , MacCrone R.K. New York: Academic Press; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Murtage, B., (1981) Advanced Linear Programming, , New York: McGraw-Hill; Chátal, V., (1990) Linear Programming, , New York: W. H. Freeman; Tampieri, A., Celotti, G., Szontagh, F., Landi, E., Sintering and characterisation of hydroxyapatite and tricalcium phosphates with control of their strength and phase porosity (1997) J Mater Sci, 8, pp. 29-37; Knowles, J.K., Development of hydroxyapatite with enhanced mechanical properties: Effect of high glass additions on mechanical properties and phase stability of sintered hydroxyapatite (1994) Br Ceram Trans, 93, pp. 100-103; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , Japanese Association of Apatite Science. Tokyo: Takayama Press System Center Co. Inc; Sax, M., Zografou, C., Telle, R., Kalawrytimos, G., Properties of sintered apatite ceramics (1995) Ceramic Processing Science and Technology, Ceramic Transactions, 51, pp. 701-705. , In: Hausner H, editor; Katz, J.L., Akers, A.S., Germiller, J.A., Obremski, S.M., Singh, S., The elastic properties of apatites and tricalcium phosphates-calcite mixtures (1989) Bioceramics, 1, pp. 86-91; Dewith, G., Vandijk, J.A., Hattu, N., Prijs, K., Preparation, microstructure and mechanical properties of dense polycrystalline hydroxyapatite (1981) J Mater Sci, 16, pp. 1592-1598; Akao, M., Aoki, H., Kato, K., Mechanical properties of sintered hydroxyapatite for prosthetic applications (1981) J Mater Sci, 16, pp. 809-812
Keywords: article; Biocompatible Materials; Ceramic matrix composites; Chemical analysis; chemical composition; composite graft; Duckworth-Knudsen model; Elastic moduli; Elasticity; glass; hydroxyapatite; Hydroxyapatite glass composites; Hydroxyapatites; Implants (surgical); Mathematical models; Microstructure; Molecular Structure; Phosphate minerals; Phosphates; porosity; priority journal; Shear modulus; shear stress; young modulus; Young's modulus

Remote foetal heart rate acquisition and analysis - Marques, P.; Marques de Sa, J.P.; Bernardes, J.; Sousa, P. (Computers in CardiologyComput Cardiol, 2000)
The remote foetal monitoring and analysis is part of INTERCARE project - an integrated healthcare system applied to Electrocardiography and Cardiotocography. Its aim is to provide low cost and wide spread technological infrastructure that supports an integrated healthcare system to users and healthcare providers. This paper illustrates the work done in the cardiotocography area. We have developed a system for remote acquisition and analysis of FHR. The system uses a portable 'foetal detector' which can be used by the pregnant woman to acquire the heart beats. This detector sends a modulated audio signal via the telephone line or a computer connected to Internet. At the processing end the signal received by the telephone can be switched to the computer sound acquisition board. The signal is then processed by an application that reads from the soundcard. Due to the noise added by devices and telephone lines, the signal is filtered using optimal FIR filters and is decimated until its band of interest covers the peaks of the heart sounds. Next the signal is processed by a specially developed adaptive correlation algorithm in order to obtain the heart beat instants. The whole process operates in real time. The adaptive correlation algorithm performs a continuous adjustment of the heart beat template and threshold detection levels.
Conference code: 45063Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: COCADLanguage of Original Document: EnglishCorrespondence Address: Marques, P.; INEB - Instituto de Engenharia, Biomedica, Porto, Portugal
Keywords: Adaptive algorithms; Adaptive correlation algorithm; Cardiology; Cardiotocography; Client server computer systems; Data acquisition; Data warehouse; Database systems; Electrocardiography; FIR filters; Foetal heart rate; Internet; Patient monitoring; Remote foetal monitoring; Signal filtering and prediction; Sonoscope; Spurious signal noise; Telephone

Structural insights of glass-reinforced hydroxyapatite composites by Rietveld refinement - Lopes, M.A.; Knowles, J.C.; Santos, J.D. (BiomaterialsBiomaterials, 2000)
Phase transformations and interstitial and/or substitution of trace elements during the liquid-phase sintering process of P 2O 5-CaO-MgO glass-reinforced hydroxyapatite (GR-HA) composites were examined by X-ray diffraction and Rietveld analyses. Using the Rietveld method for structure refinement, changes in the lattice parameters of the two main phases of the composites, hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP), as well as changes in several bond lengths and in the occupancy of the hydroxyl oxygen site in the HA phase structure were assessed. The glasses gave rise to formation of between approximately 45 and 50% of β-TCP, with evidence for the Mg 2+ enhancing the formation of β-TCP. Between 1300 and 1350°C, the β-TCP inverts to α-TCP, without further decomposition of the residual HA. The glasses showed evidence for stabilisation of the hydroxyl group located in the hydroxyl channels. This is supported by measurements of the hydroxyl channel radius (R(c)), the Ca 2-OH bond length and the hydroxyl oxygen occupancy (O(occ)). Results showed that the Mg 2+ containing glasses induced the β-TCP phase formation in the structure of GR-HA composites and retarded the β-TCP into α-TCP transformation at higher temperatures. The chemical composition of the P 2O 5 glasses also induces modifications in the lattice parameters of the crystallographic phases present in the microstructure of the composites. This suggests some substitution of Mg 2+-for-Ca 2+ in the β-TCP structure during the liquid-phase sintering process. Copyright (C) 2000 Elsevier Science Ltd. Phase transformations and interstitial and/or substitution of trace elements during the liquid-phase sintering process of P 2O 5-CaO-MgO glass-reinforced hydroxyapatite (GR-HA) composites were examined by X-ray diffraction and Rietveld analyses. Using the Rietveld method for structure refinement, changes in the lattice parameters of the two main phases of the composites, hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP), as well as changes in several bond lengths and in the occupancy of the hydroxyl oxygen site in the HA phase structure were assessed. The glasses gave rise to formation of between approximately 45 and 50% of β-TCP, with evidence for the Mg 2+ enhancing the formation of β-TCP. Between 1300 and 1350 °C, the β-TCP inverts to α-TCP, without further decomposition of the residual HA. The glasses showed evidence for stabilization of the hydroxyl group located in the hydroxyl channels. This is supported by measurements of the hydroxyl channel radius (R c), the Ca 2-OH bond length and the hydroxyl oxygen occupancy (O occ). Results showed that the Mg 2+ containing glasses induced the β-TCP phase formation in the structure of GR-HA composites and retarded the β-TCP into α-TCP transformation at higher temperatures. The chemical composition of the P 2O 5 glasses also induces modifications in the lattice parameters of the crystallographic phases present in the microstructure of the composites. This suggests some substitution of Mg 2+-for-Ca 2+ in the β-TCP structure during the liquid-phase sintering process.
Cited By (since 1996): 14Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(00)00068-5PubMed ID: 10919694Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Instituto Engenharia Biomedica, Laboratorio de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: jdsantos@alf.fe.up.ptChemicals/CAS: beta-tricalcium phosphate; Biocompatible Materials; Calcium Phosphates; Hydroxyapatites; Magnesium, 7439-95-4; Trace Elements; tricalcium phosphate, 7758-87-4References: Elliot, J.C., Structure and chemistry of the apatites and other calcium orthophosphates (1994) Studies in Inorganic Chemistry, 18. , Amsterdam: Elsevier Science;Okazaki, M., Sato, M., Computer graphics of hydroxyapatite and β -tricalcium phosphate (1990) Biomaterials, 11, pp. 573-578; Hench, L.L., Wilson, J., An introduction to bioceramics (1993) Advanced Series in Ceramics, 1, pp. 139-180. , editors. Singapore: World Scientific; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15 (1), pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass-reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39 (2), pp. 244-251; Lopes, M.A., Santos, J.D., Monteiro, F.J., Serro, A.P., Saramago, B., Hydrophobicity, surface tension, and zeta potential of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Li, P., (1993) In Vitro and in Vivo Calcium Phosphate Induction on Gel Oxides, , PhD thesis, Leiden, Offsetdrukkerij Haveka B.V. ed; Hagen, A.R., Structural features of biologically involved phosphates (1970) Acta Odontol Scand, 58, pp. 149-173; Narasaraju, T.S.B., Phebe, D.E., Review: Some physicochemical aspects of hydroxylapatite (1996) J Mater Sci, 31, pp. 1-21; Kay, M.I., Young, R.A., Posner, A.S., The crystal structure of hydroxyapatite (1964) Nature, 204, pp. 1050-1052; Montel, G., Bonel, G., Heughebaert, J.C., Trombe, J.C., Rey, C., New concepts in the composition, crystallisation and growth of the mineral component of calcified tissues (1981) J Crystal Growth, 53, pp. 74-99; Fanovich, M.A., Castro, M.S., Porto López, J.M., Analysis of the microstructural evolution in hydroxyapatite ceramics by electrical characterisation (1999) Ceramics Int, 25, pp. 517-522; Bigi, A., Falini, G., Foresti, E., Gazzano, M., Ripamonti, A., Roveri, N., Rietveld structure refinements of calcium hydroxyapatite containing magnesium (1996) Acta Crystallogr, 52, pp. 87-92; Okazaki, M., Sato, M., Takahashi, J., Space-cutting model of hydroxyapatite (1995) Biomaterials, 16, pp. 45-49; Ravalgloli, A., Krajewski, A., (1992) Bioceramics, pp. 16-59. , London: Chapman & Hall; Okazaki, M., Takahashi, J., Kimura, H., Unstable behavior of magnesium-containing hydroxyapatites (1986) Caries Res, 20, pp. 324-331; Kotani, S., Fijita, Y., Kitsugi, T., Nakamura, T., Yamamuro, T., Ohtsuki, C., Kokubo, T., Bone bonding mechanism of β -tricalcium phosphate (1991) J Biomed Mater Res, 25, pp. 1303-1315; Eanes, E.D., Thermochemical studies on amorphous calcium phosphate (1970) Calcif Tiss Res, 5, pp. 133-145; De Groot, K., Klien, P.A.T., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., Chemistry of calcium phosphate bioceramics (1990) Handbook of Bioactive Ceramics, 2, pp. 3-16. , T. Yamamuro, L.L. Hench, Wilson J. Boca Raton, FL: CRC Press; Legeros, R.Z., Calcium phosphates in oral biology and medicine (1991) Monographs in Oral Science, 15, pp. 87-107. , New York: Karger
Keywords: article; Biocompatible Materials; Biomedical engineering; Calcium Compounds; calcium phosphate; Calcium phosphates; Chemical bonds; chemical composition; Composition effects; Crystal lattices; Crystal microstructure; crystal structure; Crystallization; decomposition; Fiber reinforced materials; glass; Glass fibers; Glass-reinforced hydroxyapatite; Glass-reinforced hydroxyapatite composites; hydroxyapatite; Hydroxyapatites; Implants (surgical); Liquid-phase sintering; Magnesium; Mg-apatites; Models, Molecular; phase transition; Phase transitions; Phosphate minerals; priority journal; Rietveld refinement; Rietveld refinement analysis; Sintering; spectacles; structure analysis; temperature; Thermodynamics; Trace Elements; Tricalcium phosphate; X ray analysis; X ray crystallography; β-TCP

CaO-P 2O 5 glass hydroxyapatite double-layer plasma-sprayed coating: In vitro bioactivity evaluation - Ferraz, M.P.; Monteiro, F.J.; Santos, J.D. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
Double-layer composite coatings composed of a P 2O 5-based glass/Ca 10(PO 4) 6(OH) 2 (HA) mixture top layer and a simple HA underlayer, on Ti-6AI-4V substrates, were prepared using a plasma-spraying technique. The in vitro bioactivity of these coatings was assessed by immersion testing in simulated body fluid. Both scanning electron microscopy (SEM) analysis and the ionic solution changes followed by atomic absorption spectroscopy and the molybdenum blue method demonstrated that these composite coatings induce a faster surface Ca-P layer formation than the simple HA coatings used as a control. X-ray photoelectron spectroscopy (XPS) analysis demonstrated that the Ca-P layer formed was apatite. The combination of SEM and XPS analyses showed that the apatite layer was a calcium-deficient hydroxyapatite with a Ca/P ranging from 1.3 to 1.4 with CO 3 2- groups contained in the structure. Double-layer composite coatings composed of a P 2O 5-based glass/Ca 10(PO 4) 6(OH) 2 (HA) mixture top layer and a simple HA underlayer, on Ti-6AI-4V substrates, were prepared using a plasma-spraying technique. The in vitro bioactivity of these coatings was assessed by immersion testing in simulated body fluid. Both scanning electron microscopy (SEM) analysis and the ionic solution changes followed by atomic absorption spectroscopy and the molybdenum blue method demonstrated that these composite coatings induce a faster surface Ca-P layer formation than the simple HA coatings used as a control. X-ray photoelectron spectroscopy (XPS) analysis demonstrated that the Ca-P layer formed was apatite. The combination of SEM and XPS analyses showed that the apatite layer was a calcium-deficient hydroxyapatite with a Ca/P ranging from 1.3 to 1.4 with CO 3 2- groups contained in the structure.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(19990615)45:4<376::AID-JBM13>3.0.CO;2-SLanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; Departamento Engenharia Metalurgica, FEUP, Universidade do Porto, R. dos Bragas, 4099 Porto Codex, PortugalChemicals/CAS: Alloys; Calcium, 7440-70-2; CaO-SiO2-P2O5-CaF2 glass; Coated Materials, Biocompatible; Durapatite, 1306-06-5; Phosphates; Powders; Resin Cements; Solutions; titanium alloy (TiAl6V4), 12743-70-3; Titanium, 7440-32-6References: Denissen, H., Mangano, C., Venini, G., (1985) Hydroxylapatite Implants., , Padua: Piccin Nuova Libraria, S.P.A;Van Raemdonck, W., Ducheyne, P., De Meester, P., Calcium phosphate ceramics (1984) Metal and Ceramic Biomaterials, pp. 143-166. , Ducheyne P, Hastings GW, editors, Boca Raton, FL: CRC Press; Legeros, R.Z., Incorporation of magnesium in synthetic and biological apatites (1994) Tooth Enamel IV., pp. 32-36. , Fearnead RW, editor. Amsterdam: Elsevier Science; Jha, L.J., Best, S.M., Knowles, J.C., Rehman, I., Santos, J.D., Bonfield, W., Preparation and characterization of fluoride-substituted apatites (1997) J Mater Sci Mater Med, 8, pp. 185-191; Geesink, R.G.T., Degroot, K., Chemical implant fixation using hydroxyl-apatite coatings (1987) Clin Orthop, 2, pp. 147-170; Radin, S., Ducheyne, P., The effect of plasma sprayed induced changes in the characteristics on the in vitro stability of calcium phosphate ceramics (1990) Transactions of the 16th Annual Meeting of the Society for Biomaterials XIII, pp. 128-130; Cook, S.D., Thomas, K.A., Hydroxyapatite coated porous titanium for use as an orthopaedic biologic attachment (1989) Clin Orthop, 230, pp. 303-312; McPherson, R., Gane, N., Bastow, T.J., Structural characterization of plasma-sprayed hydroxylapatite coatings (1995) J Mater Sci Mater Med, 6, pp. 327-334; De Groot, K., Geesink, R., Klein, C.P.A.T., Serekian, P., Plasma sprayed coatings of hydroxylapatite (1987) J Biomed Mater Res, 21, pp. 1375-1381; Ravagliolli, A., Krajewszki, A., Laudadio, P., Presutti, L., Cunsolo, E., Martinetti, R., About ceramics for stapedial prostheses and the ossicular chain (1992) Fifth International Symposium on Ceramics in Medicine-Bioceramics 5, pp. 451-458. , Yamamuro T, Kokubo T, Nakamura T, editors. Kyoto: Kobunshi Kankokai; Hastings, G.W., Daily, D., Hydroxyapatite coatings (1989) First International Symposium on Ceramics in Medicine-Bioceramics 1, pp. 355-358. , Oonishi H, Aoki H, Sawai K, editors. Tokyo: Ishiyaku EuroAmerica; Aoki, H., Medical applications of hydroxyapatite (1991) Science and Medical Applications of Hydroxyaptite, pp. 175-192. , Aoki H, Sawai K, editors. Tokyo: Takyama Press System Centre; Rey, C., Calcium phosphate biomaterials and bone mineral: Differences in composition, structures and properties (1990) Biomaterials, 11, pp. 13-15; Evans, G., Behiri, J., Currey J, B.W., Microhardness and young's modulus in cortical bone exhibiting a wide range of mineral volume fractions, and in a bone analogue (1990) J Mater Sci Mater Med, 1, pp. 38-43; Rey, C., Froche, M., Heughebaert, M., Heughebaert, J.C., Lacout, J.L., Vignoles, M., Apatite chemistry in biomaterial preparation, shaping and biological behaviour (1991) Fourth International Symposium on Ceramics in Medicine-Bioceramics 4, pp. 57-60. , Bonfield W, Hastings GW, Tanner KE, editors. London: Butterworth-Heinemann; Knowles, J.C., Talal, S., Santos, J.D., Sintering effects in a glass reinforced hydroxyapatite (1996) Biomaterials, 17, pp. 1437-1442; Kokubo, T., Hayashi, T., Sakka, S., Kitsugi, T., Yamamuro, T., Takagi, M., Shibuya, T., Surface structure of a load bearable bioactive glass-ceramic A-W (1981) High Tech Ceramics, pp. 175-184. , Vicenzini P, editor. Amsterdam: Elsevier Science Publisher BV; Hench, L., Anderson, O.H., LaTorre, G.P., The kinetics of bioactive ceramics. Part III: Surface reactions for bioactive glasses compared with inactive glass (1991) Fourth International Symposium on Ceramics in Medicine-Bioceramics 4, , Bonfield W, Hastings GW, Tanner KE, editors. London: Butterworth-Heinemann; 155-162; Daculsi, G., LeGeros, R.Z., Heughebart, M., Barbieux, I., Formation of a carbonate apatite crystals after implantation of calcium phosphate ceramics (1990) Calcif Tissue Int, 46, pp. 20-27; Kokubo, T., Ito, S., Huang, Z.T., Hayashi, T., Sakka, S., Kitsugi, T., Yamamuro, T., Ca-P rich layer formed on high strength bioactive glass-ceramic A-W (1990) J Biomed Mater Res, 24, pp. 331-343; Ducheyne, P., Radin, S., Ishikawa, K., Kim, C.S., Dissolution and precipitation of calcium phosphate phases on biomaterials correlates with in vivo bioactivity (1991) Fourth International Symposium on Ceramics in Medicine-Bioceramics 4, pp. 135-144. , Bonfield W, Hastings GW, Tanner KE, editors. London: Butterworth-Heinemann; Rey, C., Hina, A., Amrah-Bouali, S., Ranz, X., Surface reactions of calcium-phosphate bioceramics, comparison with bone mineral surface chemistry (1995) Fourth Euro Ceramics., 8, pp. 301-312. , Ravaglioli A, editor. Faenza: Gruppo Editoriale Faenza Editrice; Van Blitterswijk, C.A., Grote, J.J., Kuypers, W., Blok-Van Hoek, C.J.G., Daems, W.T., Bioreactions at the tissue/hydroxyapatite interface (1985) Biomaterials, 6, pp. 243-251; Ducheyne, P., Bioceramics: Material characteristics versus in vivo behavior (1987) J Biomed Mater Res, 21, pp. 219-236; Hyakuna, K., Yamamuro, T., Kotoura, Y., Oka, M., Nakamura, T., Kitsogi, T., Kokubo, T., Kushitani, H., Surface reactions of calcium phosphate ceramics to various solutions (1990) J Biomed Mater Res, 24, pp. 471-488; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions: Structure and properties of the composites (1995) J Mater Sci Mater Med, 6, pp. 348-352; Tanahashi, M., Yao, T., Kokubo, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., Apatite coated on organic polymers by biomimetic process: Improvement in adhesion to substrate by HC1 treatment (1995) J Mater Sci Mater Med, 6, pp. 319-326; Neo, M., Nakamura, T., Yamamuro, T., Ohtsuki, C., Kokubo, T., Bando, Y., A comparative study of ultrastructures of the interfaces between four kinds of surface-active ceramic and bone (1992) J Biomed Mater Res, 26, pp. 1419-1432; Li, P., Ohtsuki, C., Kokubo, T., Nakanishi, K., Soga, N., Nakamura, T., Yamamuro, T., Process of formation of bone-like apatite layer on silica gel (1993) J Mater Sci Mater Med, 4, pp. 127-131; Santos, J.D., Jha, L.J., Monteiro, F.J., Surface modifications of glass-reinforced hydroxyapatite composites (1995) Biomaterials, 16, pp. 521-526; Neo, M., Kotani, S., Fujita, Y., Yamamuro, T., Bando, Y., Ohtsuki, C., Kokubo, T., Differences in ceramic-bone interface between surface-active ceramics and resorbable ceramics: A study by scanning and transmission electron microscope (1992) J Biomed Mater Res, 26, pp. 255-267; Li, P., Yang, Q., Zhang, F., Kokubo, T., The effect of residual glassy phase in a bioactive glass-ceramic on the formation of its surface apatite layer in vitro (1992) J Mater Sci Mater Med, 3, pp. 452-456; Kotani, S., Fujita, Y., Kitsugi, T., Nakamura, T., Yamamuro, T., Bone bonding mechanism of β-tricalcium phosphate (1991) J Biomed Mater Res, 25, pp. 1303-1315; Daculsi, G., LeGeros Rz, H.M., Barbieux, I., Formation of carbonate-apatite crystals after implantation of calcium phosphate ceramics (1990) Calcif Tissue Int, 46, pp. 20-27; Silva, P.L., Monteiro, F.J., Santos, J.D., Knowles, J.C., Adhesion and microstructural characterisation of plasma sprayed hydroxyapatite-glass ceramic coatings onto Ti-6Al-4V substrates (1998) Surf Coatings Technol, 102, pp. 191-196; Kokubo, T., Kushitani, H., Ohtsuki, C., Sakka, S., Yamamuro, T., Chemical reaction of bioactive glass and glass-ceramics with a simulated body fluid (1992) J Biomed Mater Res, 3, pp. 79-83; Blakeslee, D.M., Dal-Favero, M.E., (1997) NIST X-ray Photoelectron Spectroscopy Database, , Gaitherburg, MD: National Institute of Standards and Technology; Anderson, O.H., Kangasniemi, I., Calcium phosphate formation at the surface of bioactive glass in vitro (1991) J Biomed Mater Res, 25, pp. 1019-1030; Santos, J.D., Jha, L.J., Monteiro, F.J., In vitro calcium phosphate formation on SiO 2-Na 2O-CaO-P 2O 5 glass reinforced hydroxyapatite composite: A study by XPS analysis (1996) J Mater Sci Mater Med, 7, pp. 181-185; Verhoeven, J.A.T., Van Doveren, H., An XPS investigation of the interface of methane, ethyne, ethene and ethane with barium surface (1982) Surf Sci, 123, pp. 369-383
Keywords: alloy; Alloys; Apatite; article; Atomic absorption spectroscopy; Atomic spectroscopy; Bioactivity; Biocompatibility; biomaterial; Biomaterials; Biomedical engineering; Body fluids; Calcium; Calcium Compounds; CaO SiO2 P2O5 CaF2 glass; CaO-SiO2-P2O5-CaF2 glass; Chemical analysis; chemical composition; Coated Materials, Biocompatible; Double layer coatings; Double-layer coatings; Durapatite; film; glass; Glass plasma spraying; human; Humans; hydroxyapatite; immersion; implant; in vitro study; Ionic solution changes; Magnesium; materials testing; Molybdenum blue; Multilayers; Particle Size; phosphate; Phosphate minerals; Phosphates; Phosphorus Compounds; phosphorus pentoxide; Plasma spraying; potassium; powder; Powders; resin cement; Resin Cements; Scanning electron microscopy; Sodium; solution and solubility; Solutions; structure analysis; Substrates; Surface Properties; surface property; thickness; Tissue; Titanium; titanium alloy (TiAl6V4); Titanium alloys; X ray photoelectron spectroscopy

Enhancement of the mechanical properties of a high-density polyethylene - Kalay, G.; Sousa, R.A.; Reis, R.L.; Cunha, A.M.; Bevis, M.J. (Journal of Applied Polymer ScienceJ. Appl. Polym. Sci., 1999)
This paper describes the process optimization in injection molding of high-density polyethylene (HDPE). Both conventional injection molding and shear controlled orientation (SCORIM) were employed in processing. The process optimization was based on design of experiments and complemented with analysis of variance. Mechanical characterization was carried out by tensile testing. Wide-angle X-ray diffraction and differential scanning calorimetry were used for the structural characterization of the moldings. High-density polyethylene exhibits 7.2 GPa Young's modulus and 155 MPa of ultimate tensile strength following the application of SCORIM processing. These results account for a fourfold increase in Young's modulus and a fivefold increase in ultimate tensile strength compared to conventional injection molding. The maintenance of toughness while enhancing stiffness and strength of the SCORIM moldings is attributable to an oriented morphology developed during shear flow, i.e., shish-kebab structure. The frequency of shearing action has the strongest influence on the morphology development. It is also demonstrated that the studied parameters are very much interdependent. It is possible to achieve substantial gains in mechanical properties of HDPE in SCORIM processing without causing a substantial increase in cycle time.
Cited By (since 1996): 48Export Date: 21 November 2012Source: ScopusCODEN: JAPNAdoi: 10.1002/(SICI)1097-4628(19990919)73:12<2473::AID-APP16>3.0.CO;2-OLanguage of Original Document: EnglishCorrespondence Address: Kalay, Gurhan; Brunel Univ, Middlesex, United KingdomReferences: Kalay, G., Allan, P.S., Bevis, M.J., (1997) Kunststoffe, 87, p. 6;Kalay, G., Bevis, M.J., (1997) J Polym Sci Polym Phys, 35, p. 241; Kalay, G., Bevis, M.J., (1997) J Polym Sci Poly Phys, 35, p. 265; Kalay, G., Bevis, M.J., (1997) J Polym Sci Polym Phys, 35, p. 415; Kalay, G., Ogbonna, C.I., Allan, P.S., Bevis, M.J., (1995) Trans IChemE Part A Chem Eng Res Design, 73, p. 798; Keller, A., Kolnaar, H., (1997) Mat Sci Technol, 18, p. 191; Allan, P.S., Bevis, M.J., (1987), British Patent 2170-140-BAllan, P.S., Bevis, M.J., (1990) Composites Manufact, 1, p. 79; Wang, L., Allan, P.S., Bevis, M.J., (1995) Plastics Rubber Composites Process Appl, 23, p. 139; Gil, E.M., Kalay, G., Allan, P.S., Bevis, M.J., (1997) Polymer Process Engineering 97, pp. 40-54. , Coates, P. D., Ed.; The Institute of Materials: London; Ogbonna, C.I., Kalay, G., Allan, P.S., Bevis, M.J., (1995) J Appl Polym Sci, 58, p. 2131; Kubát, J., Månson, J.A., (1983) Polym Eng Sci, 23, p. 86; Kubát, J., Månson, J.A., Rigdahl, M., (1983) Polym Eng Sci, 23, p. 877; Boldizar, A., Kubát, J., Rigdahl, M., (1990) J Appl Polym Sci, 39, p. 63; Guan, Q., Shen, K., Ji, J., Zhu, J., (1995) J Appl Polym Sci, 55, p. 1797; Guan, Q., Shen, K., (1995) Z. Chem J Chinese Univers, 16, p. 1129; Ross, J.P., (1998) Taguchi Techniques for Quality Engineering, , McGraw-Hill: New York; Schmidt, S.R., Launsby, R.G., (1994) Understanding Industrial Designed Experiments, 4th Ed., , Air Academy Press: CO; Montgomery, D.C., (1991) Design and Analysis of Experiments, 3rd Ed., , Wiley: New York
Keywords: differential scanning calorimetry; Elastic moduli; High density polyethylenes; Injection molding; morphology; Optimization; Shear controlled orientation in injection molding; Shear flow; Shish kebab structure; Stiffness; Strength of materials; tensile strength; Tensile testing; Toughness; Wide angle X ray diffraction; X ray diffraction analysis

Flow cytometry analysis of effects of glass on response of osteosarcoma cells to plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings - Ferraz, M.P.; Knowles, J.C.; Olsen, I.; Monteiro, F.J.; Santos, J.D. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
Multilayered coatings composed of mixtures of hydroxyapatite (HA) and P 2O 5-based bioactive glasses offer potential clinical benefits in orthopedic and dental surgery. In this study double-layer plasma-sprayed coatings were prepared and the biological response evaluated in tissue culture using two human osteosarcoma cell lines, MG63 and HOS TE85 (HOS). The cells were cultured on the materials and the effects on cell growth were determined using a spectrophometric assay of a mitochondrial enzyme that is active in viable cells. While none of the materials influenced the growth of the MG63 cells, the HOS cells appeared to undergo less proliferation on all the HA materials. Flow cytometry analysis was carried out using rabbit antibodies against osteonectin, osteopontin, bone sialoprotein, fibronectin, and collagen type I to measure the effects of the materials on key cellular functions. The results showed that the materials downregulated the expression of these extracellular matrix antigens by MG63 cells whereas they had less effect on the HOS cells compared to the same cells incubated on a plastic surface. Notably, with both cell lines the composite with the higher percentage of glass restored the production of connective tissue proteins to levels that were more similar to those present in the control cells. In this study, double-layer plasma-sprayed coatings were prepared and the biological response evaluated in tissue culture using two human osteosarcoma cell lines, MG63 and HOS TE85 (HOS). The materials downregulated the expression of the extracellular matrix antigens by MG63 cells whereas they had less effect on the HOS cells compared to the same cells incubated on a plastic surface. Notably, with both cell lines the composite with the higher percentage of glass restored the production of connective tissue proteins to levels that were more similar to those present in the control cells.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(19991215)47:4<603::AID-JBM18>3.0.CO;2-6PubMed ID: 10497297Language of Original Document: EnglishCorrespondence Address: Olsen, I.; Department of Periodontology, Eastman Dental Institute, University of London, 256 Gray's Inn Road, London WC1X 8LD, United KingdomChemicals/CAS: Bone Substitutes; Coated Materials, Biocompatible; HydroxyapatitesReferences: Passuti, N., Daculsi, G., Martin, S., Macroporous calcium phosphate ceramics for long bone surgery in human and dogs - Clinical and histological studies (1990) Clinical Implant Materials, pp. 255-258. , Soltesz V, Lee A, editors. Amsterdam: Elsevier Sciesnce Publishers;Legeros, R., Calcium phosphate materials in restorative dentistry. A review (1988) Adv Dent Res, 2, pp. 164-180; Hench, L.L., Bioactive ceramics: From concept to clinic (1992) J Am Ceram Soc, 74, pp. 1487-1510; Conish, H., Aoki, H., Sawai, K., (1981) Science and Medical Applications of Hydroxyapatite, , Tokyo: Takyama Press System Centre Co; Raemdonick, W., Ducheyne, P., Meester, P., Calcium phosphate ceramics (1984) Metal and Ceramic Materials, pp. 143-166. , Ducheyne P, Hastings GW, editors. Boca Raton, FL: CRC Press; Rey, C., Freche, M., Heughebaert, M., Vignoles, M., Apatite chemistry in biomaterial preparation, shaping and biological behaviour (1991) 4th Symposium on Ceramics in Medicine - Bioceramics, 4, pp. 57-64. , Bonfield W, Hastings GW, Tanner KE, editors. London: Butterworth-Heinemann; Nagase, M., Abe, Y., Udagwa, E., Toxicity of silica-containing calcium phosphate glasses demonstrated in mice (1992) Biomaterials, 13, pp. 172-175; Burnie, J., Gilchrist, T., Controlled released glass - A new biomaterial (1983) Ceramics in Surgery, pp. 169-176. , Vicenzini P, editor. Amsterdam: Elsevier Science Publishers; Jha, L.J., Santos, J.D., Knowles, J.C., Characterization of apatite layer formation on P 2O 5-CaO, P 2O 5-CaO-Na 2O, P 2O 5-CaO-Na 2O-Al 2O 3 glass hydroxyapatite composites (1996) J Biomed Mater Res, 31, pp. 481-486; Rawlings, R.D., Rogers, P.S., Stokes, P.M., Glass-ceramics containing apatite (1987) High Tech Ceramics, pp. 73-82. , Vicenzini P, editor. Amsterdam: Elsevier Science Publishers; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterization of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Santos, J.D., Lakhan, J.J., Monteiro, F.J., Surface modifications of glass-reinforced hydroxyapatite composites (1995) Biomaterials, 16, pp. 521-526; Ferraz, M.P., Monteiro, F.J., Santos, J.D., In vitro bioactivity and osteocompatibility evaluation of plasma sprayed hydroxyapatite/glass composite coatings onto Ti-6AL-4V substrates (1997) 9th International Conference on Biomedical Engineering, pp. 557-559. , Goh JCH, editor. Singapore: BAC Printers; Klein, C.P.A.T., Patka, P., Van Der Lubbe, H.B.M., Plasma-sprayed coatings of tetracalcium phosphate, hydroxylapatite, and α-TCP on titanium alloy: An interface study (1991) J Biomed Mater Res, 25, pp. 53-65; Jansen, J.A., Van Der Waerden, J.P., Wolke, J.G., Histologic investigation of the biologic behavior of different hydroxyapatite plasma-sprayed coatings in rabbits (1993) J Biomed Mater Res, 14, pp. 603-610; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., The ultrastructure of the bone-hydroxyapatite interface in vitro (1992) J Biomed Mater Res, 26, pp. 1365-1382; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., Comparative biological properties of HA plasma-sprayed coatings having different crystallinities (1994) J Mater Sci Mater Med, 5, pp. 11-17; Lugscheider, E., Knepper, M., Heimberg, B., Dekker, A., Kirkpatrick, C.J., Cytotoxicity investigations of plasma-sprayed calcium-phosphate coatings (1994) J Mater Sci Mater Med, 5, pp. 371-375; Courteney-Harris, R.G., Kayser, M.V., Downes, S., Comparison of the early production of extracellular matrix on dense hydroxyapatite and hydroxyapatite-coated titanium in cell and organ culture (1995) Biomaterials, 16, pp. 489-495; Labat, B., Chanson, A., Frey, J., Effects of γ-alumina and hydroxyapatite coatings on the growth and metabolism of human osteoblasts (1995) J Biomed Mater Res, 29, pp. 1397-1401; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., Adult human bone cells derived from jaw bones cultured on plasma-sprayed or polished surfaces to titanium or hydroxyapatite discs (1996) J Mater Sci Mater Med, 7, pp. 21-28; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Ariola, C.R., Granchi, D., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin Biomater, 15, pp. 173-190; Puleo, D.A., Preston, K.E., Shaffer, J.B., Bizios, R., Examination of osteoblast-orthopaedic biomaterial interactions using molecular techniques (1993) Biomaterials, 14, pp. 111-114; Clifford, C.J., Downes, S., A comparative study of the use of colorimetric assays in the assessment of biocompatibility (1996) J Mater Sci Mater Med, 7, pp. 637-643; Macey, M.G., (1994) Flow Cytometry - Clinical Applications, , Oxford, UK: Blackwell Scientific Publications; Shapiro, H.M., (1995) Practical Flow Cytometry, , New York: Wiley-Liss; Melamed, M.R., Lindmo, T., Mendelsohn, M.L., (1990) Flow Cytometry and Sorting, , New York: Wiley-Liss; Muirhead, K.A., Horan, P.K., Applications of flow cytometry to tissue culture systems (1983) Adv Cell Culture, 3, pp. 57-91; Corver, W.E., Cornelisse, C.J., Fleuren, G.J., Simultaneous measurement of two cellular antigens and DNA using fluorescein-isothiocyanate, R-phycoerythrin and propidium iodide on a standard FACScan (1994) Cytometry, 15, pp. 117-128; Pande, G., Kumar, N.A., Manogaran, P.S., Flow cytometric study of changes in intracellular free calcium during the cell cycle (1996) Cytometry, 24, pp. 55-63; Kamiya, I., Okuda, K., Hara, K., Flow cytometric identification and detection of Porphyromonas gingivalis by a lps specific monoclonal antibody (1994) J Periodontol, 65, pp. 309-315; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Kuru, L., Parkar, M.H., Griffiths, G.S., Newman, H.N., Olsen, I., Flow cytometry analysis of functionally distinct gingival and periodontal ligament cells (1998) J Dent Res, 77, pp. 555-564; Abraham, D., Lupoli, S., McWhirter, A., Plater-Zyberk, C., Piela, T.H., Korn, J., Olsen, I., Black, C., Expression and function of surface antigens on scleroderma fibroblasts (1991) Arthritis Rheum, 34, pp. 1164-1172; Beauchamp, J.R., Abraham, D.J., Bou-Gharios, G., Partridge, T.A., Olsen, I., Expression and function of adhesion molecules during differentiation of human skeletal muscle in culture (1992) Am J Pathol, 140, pp. 387-401; Bou-Gharios, G., Osman, J., Black, C., Olsen, I., Excess matrix accumulation in scleroderma is caused partly by differential regulation of stromelysin and TIMP-1 synthesis (1994) Clin Chim Acta, 231, pp. 69-78; Lopes, M.A., Knowles, J.C., Hing, K.A., Santos, J.D., Monteiro, F.J., Olsen, I., Biological evaluation of glass reinforced hydroxyapatite by flow cytometry (1997) 10th Symposium on Ceramics in Medicine-bioceramics, 10, pp. 575-578. , Sedel L, Rey C, editors. Cambridge, UK: University Press; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Sandy, J., Davies, M., Prime, S., Farndale, R., Signal pathways that transduce growth factor-stimulated mitogenesis in bone cells (1998) Bone, 23, pp. 17-26
Keywords: Animals; Antibodies; antigen expression; article; Bioassay; Biomaterials; Bone cells; Bone sialoprotein; Bone Substitutes; calcium phosphate; cancer cell culture; Cell Division; cell function; cell granule; cell growth; cell proliferation; Cell size; Cells; Coated Materials, Biocompatible; Collagen; collagen type 1; connective tissue; controlled study; dentistry; enzyme activity; Enzymes; Fibronectin; flow cytometry; Flow cytometry analysis; glass; Growth kinetics; human; human cell; Humans; hydroxyapatite; Hydroxyapatite-glass; Hydroxyapatites; Incubation; Mitochondrial enzyme; orthopedics; Osteoblasts; osteonectin; Osteopontin; Osteosarcoma; osteosarcoma cell; Osteosarcoma cells; Phosphates; Proliferation; Proteins; Rabbits; sialoprotein; Spectrophometric assay; Tissue culture; Tumor Cells, Cultured

Glass-reinforced hydroxyapatite composites: Fracture toughness and hardness dependence on microstructural characteristics - Lopes, M.A.; Monteiro, F.J.; Santos, J.D. (BiomaterialsBiomaterials, 1999)
Fracture toughness and hardness properties of CaO-P 2O 5 glass-reinforced hydroxyapatite composites have been assessed using indentation techniques and results calculated according to Laugier and Evans' equations. Both properties showed to be dependent upon several microstructural characteristics, namely residual porosity and the percentage of secondary β and α tricalcium phosphate phases in the structure of the composites. Composites presented a Palmqvist-type indentation crack system, which is the specific crack system addressed by Laugier's approach. Fracture toughness determinations according to Evan's equation, which is a universal one and adapted to both median and Palmqvist crack systems, did not correlate well with Laugier determinations. Copyright (C) 1999 Elsevier Science Ltd. Fracture toughness and hardness properties of CaO-P 2O 5 glass-reinforced hydroxyapatite composites have been assessed using indentation techniques and results calculated according to Laugier and Evans' equations. Both properties showed to be dependent upon several microstructural characteristics, namely residual porosity and the percentage of secondary β and α tricalcium phosphate phases in the structure of the composites. Composites presented a Palmqvist-type indentation crack system, which is the specific crack system addressed by Laugier's approach. Fracture toughness determinations according to Evan's equation, which is a universal one and adapted to both median and Palmqvist crack systems, did not correlate well with Laugier determinations.
Cited By (since 1996): 65Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(99)00112-XPubMed ID: 10535820Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratorio de Biomateriais, Instituto de Engenharia Biomedica, INEB, Rua do Campo Alegre 823, 4150 Porto, PortugalChemicals/CAS: alpha-tricalcium phosphate; Biocompatible Materials; calcium phosphate, 10103-46-5; Calcium Phosphates; Composite Resins; dicalcium phosphate anhydrous, 7757-93-9; Durapatite, 1306-06-5; monocalcium phosphate; tetracalcium phosphateReferences: Akao, M., Aoki, H., Kato, K., Mechanical properties of sintered hydroxyapatite for prosthetic applications (1981) J Mater Sci, 16, pp. 809-812;Martin, R.I., Brown, P.W., Mechanical properties of hydroxyapatite formed at physiological temperature (1995) J Mater Sci Mater Med, 6, pp. 138-143; Aoki, H., (1994) Medical Applications of Hydroxyapatite, pp. 90-173. , Tokyo, Missouri, USA: Ishiyaku EuroAmerica Inc; Yamamuro, T., Hench, L., Wilson, J., Calcium phosphate and hydroxyapatite ceramics (1990) In: Handbook of Bioactive Ceramics, 2, pp. 273-335. , editors. Florida: CRC Press Inc; Cao, W., Hench, L.L., Bioactive materials (1996) Ceramics Int, 22, pp. 493-507; Davidge, R.W., (1979) Mechanical Behaviour of Ceramics, , Cambridge: Cambridge University Press; Orange, G., Liang, K.M., Crack resistance and fracture toughness of alumina and zirconia ceramics: comparisons of notched-beam and indent techniques (1988) Science of Ceramics, 14, pp. 709-714. , Amsterdam: Elsevier; Niihara, K., Morena, R., Hasselman, D.P.H., Evaluation of K IC of brittle solids by the indentation method with low crack-to-indent ratios (1982) J Mater Sci Lett, 1, pp. 13-16; Evans, G., Fracture toughness: The role of indentation techniques (1979) Fracture Mechanics Applied to Brittle Materials ASTM STP 678, pp. 112-135. , S.W. Freiman. Blasksbaurg: American Society for Testing and Materials; Anstis, G.R., Chantikul, P., Lawn, B.R., Marshall, D.B., A critical evaluation of indentation techniques for measuring fracture toughness: I. Direct crack measurements (1981) J Am Ceram Soc, 64 (9), pp. 533-538; Chantikul, P., Anstis, G.R., Lawn, B.R., Marshall, D.B., A critical evaluation of indentation techniques for measuring fracture toughness: II. Strength method (1981) J Am Ceram Soc, 64 (9), pp. 539-543; Evans, G., Charles, E.A., Fracture toughness determinations by indentation (1976) J Am Ceram Soc, 59 (78), pp. 371-372; Marion, R.H., Use of indentation fracture to determine fracture toughness (1979) Fracture Mechanics Applied to Brittle Materials, ASTM STP 678, pp. 103-111. , S.W. Freiman. Blasksbaurg: American Society for Testing and Materials; Knowles, J.C., Talal, S., Santos, J.D., Sintering effects in a glass reinforced hydroxyapatite (1996) Biomaterials, 17, pp. 1437-1442; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass reinforced hydroxyapatite composites: Secondary phase proportions and densification effects on biaxial bending strength (1999) J Appl Biomater, , in press; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 4, pp. 649-656; Santos, D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15 (1), pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39 (2), pp. 244-251; Laugier, M.T., New formula for indentation toughness in ceramics (1987) J Mater Sci Lett, 6, pp. 355-356; Ampiro, R., (1958) Acta Anat, 3, p. 161; De With, G., Van Dijk, H.J.A., Hattu, N., Prijs, K., Preparation, microstructure and mechanical properties of dense polycrystalline hydroxyapatite (1981) J Mater Sci, 16, pp. 1592-1598; German, R.M., (1985) Liquid Phase Sintering, , Oxford: Plenum Press; Rice, R.W., Microstructure dependence of mechanical behaviour (1977) Treatise on Materials Science and Technology, 11. , MacCrone R.K. New York: Academic Press; Rice, R.W., Grain size and porosity dependence of ceramic fracture energy and toughness at 22°C (1996) J Mater Sci, 31, pp. 1969-1983; Lankford, J., Indentation microfracture in the Palmqvist crack regime: Implications for fracture toughness evaluation by the indentation method (1982) J Mater Sci Lett, 1, pp. 493-495; Li, Z., Ghosh, A.A., Kobayashi, A.S., Bradt, R.C., Indentation fracture toughness of sintered silicon carbide in the Palmqvist crack regime (1989) J Am Ceram Soc, 72 (6), pp. 904-911; Lawn, R., Marshall, D.B., Hardness, toughness and brittleness: An indentation analysis (1980) J Am Ceram Soc, 62 (78), pp. 347-350; Niihara, K., A fracture mechanics analysis of indentation-induced Palmqvist crack in ceramics (1983) J Mater Sci Lett, 2, pp. 221-223; Plannel, J.A., Vallet-Regi, M., Fernandez, E., Driessens, F.C.M., Fracture toughness evaluation of sintered hydroxyapatite (1994) Bioceramics 7, Proceedings of the Seventh International Symposium on Ceramics in Medicine, pp. 18-22. , In: Andersson OH, Yli-Urpo A, editors; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , Japanese Association of Apatite Science. Tokyo: Takayama Press System Center Co. Inc; Hauber, R.A., Anderson, R.M., Engineering properties of glass-matrix composites In: Ceramics and Glasses, Engineered Materials Handbook, pp. 858-869. , USA: ASM Publication; Barsoum, M., Mechanical properties: Fast fracture (1997) Fundamentals of Ceramics. Series in Materials Science and Engineering, pp. 391-439. , New York: McGraw-Hill; Slosarczyk, A., Bia Oskorski, J., Hardness and fracture toughness of dense calcium-phosphate based materials (1998) J Mater Sci Mater Med, 9, pp. 103-108
Keywords: article; Biocompatible Materials; Biomaterials; calcium phosphate; Calcium phosphates; ceramics; Composite materials; Composite Resins; Cracks; Durapatite; Evan's equation; Fracture toughness; glass; hardness; hydroxyapatite; Hydroxyapatite-glass composites; Indentation techniques; Kinetics; Laugier equations; material state; mechanical stress; Microscopy, Electron, Scanning; Microstructure; Palmqvist crack systems; Phosphate minerals; porosity; priority journal; Stress, Mechanical; tensile strength; Tricalcium phosphate

Glass-reinforced hydroxyapatite composites: Secondary phase proportions and densification effects on biaxial bending strength - Lopes, M.A.; Monteiro, F.J.; Santos, J.D. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
CaO-P 2O 5 glasses with additions of MgO and CaF 2 were used as a sintering aid of hydroxyapatite, and glass-reinforced hydroxyapatite composites obtained. Glasses promoted significant changes in the microstructure of the composites, namely with the formation of tricalcium phosphate secondary phases, β and α-TCP. Quantitative phase analysis was performed by the Rietveld method using General Structure Analysis Software. Grain size measurements were carried out on SEM photomicrographs, using a planimetric procedure according to ASTM E 112-88. Flexural bending strength was determined from concentric ring-on-ring testing. Flexural bending strength (FBS) of glass-reinforced hydroxyapatite composites was found to be about twice or three times higher than that of unreinforced hydroxyapatite and tended to depend more on porosity and β and α-TCP secondary phases, rather than on grain size. Traces of α-tricalcium phosphate significantly enhanced the strength of the composites. Using the rule of mixtures to estimate the zero porosity bending strength, the Duckworth-Knudsen model applied to the composites gave a porosity correction factor, b, with a value of 4.02. Weibull statistics were also used to analyze biaxial strength data and the level of reinforcement obtained by comparing failure probability for the composites and for the unreinforced hydroxyapatite. Lower activation energies for grain growth were observed for the composites compared to unreinforced hydroxyapatite, which should be attributed to the presence of a liquid glassy phase that promotes atomic diffusion during the sintering process. CaO-P 2O 5 glasses with additions of MgO and CaF 2 were used as a sintering aid of hydroxyapatite, and glass-reinforced hydroxyapatite composites obtained. Glasses promoted significant changes in the microstructure of the composites, namely with the formation of tricalcium phosphate secondary phases, β and α-TCP. Quantitative phase analysis was performed by the Rietveld method using General Structure Analysis Software. Grain size measurements were carried out on SEM photomicrographs, using a planimetric procedure according to ASTM E 112-88. Flexural bending strength was determined from concentric ring-on-ring testing. Flexural bending strength (FBS) of glass-reinforced hydroxyapatite composites was found to be about twice or three times higher than that of unreinforced hydroxyapatite and tended to depend more on porosity and β and α-TCP secondary phases, rather than on grain size. Traces of α-tricalcium phosphate significantly enhanced the strength of the composites. Using the rule of mixtures to estimate the zero porosity bending strength, the Duckworth-Knudsen model applied to the composites gave a porosity correction factor, b, with a value of 4.02. Weibull statistics were also used to analyze biaxial strength data and the level of reinforcement obtained by comparing failure probability for the composites and for the unreinforced hydroxyapatite. Lower activation energies for grain growth were observed for the composites compared to unreinforced hydroxyapatite, which should be attributed to the presence of a liquid glassy phase that promotes atomic diffusion during the sintering process.
Cited By (since 1996): 28Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(1999)48:5<734::AID-JBM20>3.0.CO;2-2PubMed ID: 10490690Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB-Instituto Engenharia Biomedica, Laboratorio de Biomateriais, Rua do Campo Alegre, 823, 4150 Porto, PortugalChemicals/CAS: alpha-tricalcium phosphate; Biocompatible Materials; calcium phosphate, 10103-46-5; Calcium Phosphates; dicalcium phosphate anhydrous, 7757-93-9; Hydroxyapatites; monocalcium phosphate; tetracalcium phosphateReferences: Yamamuro, Y., Hench, L.L., Wilson, J., (1990) CRC Handbook of Bioactive Ceramics, , Boca Raton, FL: CRC;Rice, R.W., Microstructure dependence of mechanical behaviour (1977) Treatise on Materials Science and Technology, 11. , MacCrone RK, editor. New York: Academic; Rice, R.W., Grain size and porosity dependence of ceramic fracture energy and toughness at 22°C (1996) J Mat Sci, 31, pp. 1969-1983; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Wayne, S.F., Buljan, S.T., Microstructure and wear resistance of silicon nitride composites (1994) Friction and Wear of Ceramics, p. 261. , Jahanmir S, editor. New York: Marcel Dekker; Kaysser, W.A., Sprissler, M., Handwerker, C.A., Blendell, J.E., Effect of liquid phase on the morphology of grain growth of alumina (1987) J Am Ceram Soc, 70, pp. 339-343; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Soltesz, U., Ritcher, H., Kienzler, R., The concentric-ring test and its applications for determining the surface strength of ceramics (1987) High Tech Ceram, pp. 149-159. , Amsterdam: Elsevier; Murtage, B., (1981) Advance Linear Programming, , New York: McGraw-Hill; Cha'tal, V., (1990) Linear Programming, , New York: Freeman; Davidge, R.W., (1986) Mechanical Behaviour of Ceramics, , Cambridge: Cambridge Univ Press; German, R.M., (1985) Liquid Phase Sintering, , New York: Plenum; Akao, M., Aoki, H., Kato, K., Mechanical properties of sintered hydroxyapatite for prosthetic applications (1981) J Mater Sci, 16, pp. 809-812; Fanovich, M.A., Lopes, J.M.P., Influence of temperature and additives on the microstructure and sintering behaviour of hydroxyapatites with different Ca/P ratios (1998) J Mat Sci Mat Med, 9, pp. 53-60; Jarcho, M., Bolen, C.H., Bobik, J., Kay, J.F., Doremus, R.H., Hydroxyapatite synthesis and characterisation in dense polycrystalline form (1976) J Mat Sci, 11, pp. 2027-2035; Van Landuyt, P., Li, F., Keustermans, J.P., Streydio, J.M., Delnnay, F., Munting, E., The influence of high sintering temperatures on the mechanical properties of hydroxyapatite (1995) J Mat Sci Mat Med, 6, pp. 8-13; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , Japanese Association of Apatite Layer; Chawla, K.K., (1993) Ceramic Matrix Composites, , London, UK: Chapman Hall; Barsoum, M., Fundamentals of Ceramics, , New York: McGraw-Hill; 1997
Keywords: article; atom; Bending (deformation); Biocompatibility; Biocompatible Materials; Biomaterials; calcium fluoride; calcium phosphate; Calcium phosphates; Composite materials; Densification; Dental application; dentistry; Duckworth-Knudsen model; glass; Glass reinforced hydroxyapatite; Humans; hydroxyapatite; Hydroxyapatite-glass composites; Hydroxyapatites; Implants (surgical); Magnesium Oxide; mathematical analysis; Mechanical strength; Mechanics; Medical applications; Microstructure; orthopedics; Phase composition; physical chemistry; porosity; Scanning electron microscopy; Strength of materials; tensile strength; Tissue; Tricalcium phosphate

Histological effects of iron accumulation on mice liver and spleen after administration of a metallic solution - Pereira, M.C.; Pereira, M.L.; Sousa, J.P. (BiomaterialsBiomaterials, 1999)
Special attention has been focused on the toxicity of some metallic species released from implanted materials, which accumulate in vital organs over long periods of time. A set of experiments with mice was designed to investigate the individual effects caused by iron in the liver and spleen. Histological features of these organs were evaluated and slight morphological changes were observed during the treatment time suggesting a negative correlation with the duration of the iron treatment. In addition, to associate the histological changes in the organs with iron accumulation an electrochemical method, adsorptive stripping voltammetry, was chosen to quantify the iron levels in these mentioned organs. The accuracy of the proposed method was checked by atomic absorption spectrometry. Both organs showed elevated concentrations of iron, nearly twofold, 7 days after iron administration compared to control organs.Special attention has been focused on the toxicity of some metallic species released from implanted materials, which accumulate in vital organs over long periods of time. A set of experiments with mice was designed to investigate the individual effects caused by iron in the liver and spleen. Histological features of these organs were evaluated and slight morphological changes were observed during the treatment time suggesting a negative correlation with the duration of the iron treatment. In addition, to associate the histological changes in the organs with iron accumulation an electrochemical method, adsorptive stripping voltammetry, was chosen to quantify the iron levels in these mentioned organs. The accuracy of the proposed method was checked by atomic absorption spectrometry. Both organs showed elevated concentrations of iron, nearly twofold, 7 days after iron administration compared to control organs.
Cited By (since 1996): 15Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(99)00124-6PubMed ID: 10555088Language of Original Document: EnglishCorrespondence Address: Pereira, M.C.; Departamento de Engenharia Quimica, Faculdade de Engenharia, Universidade do Porto, Rua dos Bragas, 4050-123 Porto, Portugal; email: mcsp@fe.up.ptChemicals/CAS: Iron, 7439-89-6; SolutionsReferences: Rheinold, J.B., Trace elements - A selective survey (1975) Clin Chem, 21, p. 476;Crichton, R.R., Ward, R.J., Structure and molecular biology of iron binding-proteins and the regulation of free iron pools (1992) Iron and Human Diseases, pp. 23-75. , R.B. Lauffer. Boca Raton: CRC Press Inc; Lynch, S.R., Lipschitz, D.A., Bothwell, T.H., Charlton, R.W., Iron and the reticulo-endothelial system (1974) Iron in Biochemistry and Medicine, p. 563. , A. Jacobs, & M. Worwood. London: Academic Press; Black, J., Mineral metabolism (1981) Biological Performance of Materials: Fundamentals of Biocompatibility. Biomedical Engineering and Instrumentation, 8, pp. 158-168. , R. Plonsey, Katz J.L. New York: Marcel Dekker; Sutow, E.J., Pollack, S.R., The biocompatibility of certain stainless steels (1981) Biocompatibility of Clinical Implant Materials, pp. 77-98. , D.F. Williams. Boca Raton, FL: CRC Press; Winter, G.D., Tissue reactions to metallic wear and corrosion products in human patients (1974) J Biomed Mater Res Symp, 5, pp. 11-26; Winter, G.D., Wear and corrosion products in tissues and the reactions they provoke (1976) Biocompatibility of Implant Materials, pp. 28-54. , In: Williams, DF, editor London; Ferguson A.B., Jr., Laing, P.G., Hodge, E.S., The ionization of metal implants in living tissues (1960) J Bone Jt Surg a, 42, pp. 77-90; Pohler, O.E.M., Degradation of metallic orthopedic implants (1983) Biomaterials in Reconstructive Surgery, pp. 196-197. , In: Rubin LR, editor London: The C.V. Mosby Company; Lux, F., Zeisler, R., Investigations of the corrosive deposition of components of metal implants and the behaviour of biological trace elements in metallosis tissue by means of instrumental multi-element activation analysis (1974) J Radioanal Chem, 19, pp. 289-297; Traisnel, M., Le Maguer, D., Hildebrand, H.F., Iost, A., Corrosion of surgical implants (1990) Clin Mater, 5, pp. 309-318; Gosztonyi, E., (1983) Iron Metabolism, p. 339. , New York: Plenum Press; Weinberg, E.D., Cellular acquisition of iron and the iron-withholding defense against microbial and neoplastic invasion (1992) Iron and Human Diseases, pp. 179-207. , R.B. Lauffer. Boca Raton, FL: CRC Press Inc; Pereira, M.L., Pereira, M.C., Sousa, J.P., Evaluation of nickel effects on mouse liver: Tissue response and metal ion accumulation (1995) Biomed Lett, 52, pp. 235-244; Pereira, M.C., Pereira, M.L., Sousa, J.P., Evaluation of nickel toxicity on liver, spleen and kidney of mice after administration of high-dose metal ion (1998) J Biomed Mater Res, 40, pp. 40-47; Pereira, M.C., Sousa, J.P., Nickel quantification in mice organs by adsorptive cathodic stripping voltammetry using microelectrodes (1997) Electroanalysis, 9, pp. 150-154; Pereira, M.C., Pereira, M.L., Sousa, J.P., Adsorptive stripping measurements of iron accumulation in mice kidney using microelectrodes and histological features (1998) J Trace Elements Med Biol, 12, pp. 50-55; Van Den Berg, C.M.G., Huang, Z.Q., Determination of iron in seawater using cathodic stripping voltammetry proceeded by adsorptive collection with the hanging mercury drop electrode (1984) J Electroanal Chem, 177, pp. 269-280; Smith, G.K., Black, J., Estimation of in vivo type 316L stainless steel corrosion rate from blood transport and organ accumulation data (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 223-247. , A.C. Fraker, & C.D. Griffin. Philadelphia: American Society for Testing and Materials; Barbosa, M.A., (1991) Biomaterials Degradation, p. 227. , Barbosa M.A. The Netherlands: Elsevier Science Publisher; Steinemann, S.G., Corrosion of surgical implants in vivo and in vitro tests (1980) Evaluation of Biomaterials, pp. 1-34. , In: Winter GD et al., editors UK: John Wiley & Sons Inc; Smith, G.K., Systemic aspects of metallic implant degradation (1983) Biomaterials in Reconstructive Surgery, pp. 229-242. , In: Rubin LR, London: The C.V. Mosby Company; Britton, S.R., Ramm, G.A., Olynyk, J., Singh, R., O'Neill, R., Bacon, B.R., Pathophysiology of iron toxicity (1994) Progress in Iron Research, pp. 239-253. , C. et al. Hershko. New York: Plenum Press
Keywords: Absorption spectroscopy; accuracy; Adsorption; Adsorptive stripping voltametry; Adsorptive stripping voltammetry; animal experiment; animal model; animal tissue; Animalia; Animals; article; atomic absorption spectrometry; Atomic spectroscopy; bioaccumulation; biomaterial; controlled study; Corrosion; electrochemistry; histology; histopathology; Implants (surgical); Injections, Subcutaneous; Iron; iron metabolism; Kinetics; Liver; liver toxicity; male; metal implantation; Mice; morphology; mouse; nonhuman; Organ Size; potentiometry; priority journal; quantitative assay; Solutions; Spleen; Stainless steel; tissue distribution; toxicity

Hydrophobicity, surface tension, and zeta potential measurements of glass-reinforced hydroxyapatite composites - Lopes, M.A.; Monteiro, F.J.; Santos, J.D.; Serro, A.P.; Saramago, B. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
Wettability and zeta potential studies were performed to characterize the hydrophobicity, surface tension, and surface charge of P 2O 5-glass- reinforced hydroxyapatite composites. Quantitative phase analysis was performed by the Rietveld method using GSAS software applied to X-ray diffractograms. Surface charge was assessed by zeta potential measurements. Protein adsorption studies were performed using vitronectin. Contact angles and surface tensions variation with time were determined by the sessile and pendent drop techniques, respectively, using ADSA-P software. The highest (- 18.1 mV) and lowest (-28.7 mV) values of zeta potential were found for hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP), respectively, with composite materials presenting values in between. All studied bioceramic materials showed similar solid surface tension. For HA and β-TCP, solid surface tensions of 46.7 and 45.3 mJ/m 2, respectively, were obtained, while composites presented intermediate surface tension values. The dispersive component of surface tension was the predominant one for all materials studied. Adhesion work values between the vitronectin solution and HA and β- TCP were found to be 79.8 and 88.0 mJ/m 2, respectively, while the 4.0 wt % glass composites showed slightly lower values than the 2.5 wt % ones. The presence of β-TCP influenced surface charge, hydrophobicity, and protein adsorption of the glass-reinforced HA composites, and therefore indirectly affected cell-biomaterial interactions. The hydrophobicity, surface tension, and surface charge of P 2O 5-glass-reinforced hydroxyapatite (HA) composites were characterized through wettability and zeta potential studies. The highest and lowest values of zeta potential were found for HA and β-TCP. All studied bioceramic materials showed similar solid surface tension. The presence of β-TCP indirectly affected cell-biomaterial interactions.
Cited By (since 1996): 46Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(19990615)45:4<370::AID-JBM12>3.0.CO;2-0PubMed ID: 10321710Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB, University of Porto, Rua do Campo Alegre, 823, 4150 Porto, PortugalChemicals/CAS: Biocompatible Materials; Calcium Phosphates; Hydroxyapatites; Proteins; VitronectinReferences: Yamamuro, Y., Hench, L.L., Wilson, J., (1990) CRC Handbook of Bioactive Ceramics, , Boca Raton, FL: CRC Press;Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterization of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Aoki, H., Medical applications of hydroxyapatite (1991) Science and Medical Applications of Hydroxyapatite, pp. 1-214. , Aoki H, Sawai K, editors. Tokyo: Takyama Press System Center; Akao, M., Aoki, H., Kato, K., Mechanical properties of sintered hydroxyapatite for prosthetic applications (1981) J Mater Sci, 16, pp. 809-812; Davies, J.E., The importance and measurement of surface charge species in cell behaviour at the biomaterial interface (1988) Surface Characterization of Biomaterials, pp. 219-234. , Ratner BD. New York: Elsevier; Ratner, B.D., Biomaterial surfaces (1987) J Biomed Mater Res Appl Biomat, 21, pp. 59-90; Manson, S.R., Harker, L.A., Ratner, B.D., Hoffman, A.S., Evaluation of artificial surfaces with a non human primate model of arterial thrombosis (1980) J Lab Clin Med, 95, pp. 289-304; Grinnell, F., Milamand, M., Srere, P.A., Studies on cell adhesion (1972) Arch biochem biophys, 153, pp. 193-198; Chang, S.K., Hum, O.S., Moscarello, Ma., Neumann, A.W., Zing, W., Leutheusser, M.J., Ruegsegger, B., Platelet adhesion to solid surfaces: The effect of plasma proteins and substrate wettability (1997) Med Progr Technol, 5, pp. 57-66; Agathopoulos, S., Nikolopoulos, P., Determination of the energy of the interactions oxides and biological liquids (1995) Fourth Euro Ceramics, 8, pp. 319-324. , Ravaglioli A, editor; Lapin, M., Warocquier-Clérout, R., Legris, C., Degrange, M., Luizard, M.F.S., Correlation between roughness and wettability, cell adhesion and cell migration (1997) J Biomed Mater Res, 36, pp. 99-108; Williams, D.F., Bagnall, R.D., Adsorption of proteins on polymers and its role in the response of soft tissue (1998) Fundamental Aspects of Biocompatibility, 2, pp. 113-127. , Williams DF, editor. Boca Raton, FL: CRC Press; Dimitrov, S., Krachevsky, P.A., Nikolov, A.D., Noshi, H., Matsumoto, M., Contact angle measurements with sessile drops and bubbles (1991) J Colloid Interface Sci, 145, pp. 279-282; Adamson, W., (1990) Physical chemistry of surfaces. 5th edition, pp. 4-52. , New York: Wiley; Young, T., (1835) Miscellaneous Works, 1, p. 418. , Peacock G, editor London: Murray; Young, T., (1805) Philos Trans R Soc Lond, 95, p. 65; Correia, N.T., Ramos, J.M., Saramago, B., Calado, J., Estimation of the surface tension of a solid: Application to a liquid crystalline (1997) J Colloid Interface Sci, 189, pp. 361-369; Owens, D.K., Wendt, R.D., Estimation of the surface free energy of polymers (1969) J Appl Polym Sci, 13, p. 1741; Schrader, M.E., Young dupré revisited (1995) Langmuir, 11, p. 3585; Kowalchuk, R.M., Pollack, S.R., Ducheyne, P., King, L.A., Particle microelectrophoresis of calcium-deficient hydroxyapatite: Solution composition and kinetics effects (1993) J Biomed Mater Res, 27, pp. 783-790; Ducheyne, P., Kim, C.S., Pollack, S.R., The effect of phase differences on the time dependent variation of the zeta potential of hydroxyapatite (1992) J Biomed Mater Res, 26, pp. 147-168; Suzuki, T., Nishizawa, K., Yokogawa, Y., Kameyama, T., Time-dependent variation of the surface structure of bioceramics in tissue culture medium and the effect on adhesiveness of cells (1996) J Ferment Bioeng, 81, pp. 226-232; Susuki, T., Yamamoto, T., Yoriyama, M., Kameyama, T., Surface instability of calcium phosphates ceramics in tissue culture medium and the effect on adhesion and growth of anchorage-dependent animal cells (1997) J Biomed Mater Res, 34, pp. 507-517; Hay, H., (1991) Cell Biology of Extracellular Matrix. 2nd Edition, pp. 127-129. , New York: Plenum Press; Seiffert, D., Detection of vitronectin in mineralized bone matrix (1986) J Histochem Cytochem, 44, pp. 275-280; Rodan, G.A., Introduction to bone biology (1992) Bone, 12, p. 53; Young, M.E., Kerr, J.M., Ibaraki, K., Heegaard, A.M., Gehron, R.P., Structure, expression and regulation of the major matrix proteins of bone (1992) Clin Orthop Rel Res, 281, p. 275; Formigli, L., Zecchi, S., Benvenuti, S., Brandi, M.L., Cell to cell interaction on bone tissue (1992) Ann NY Acad Sci, 673, p. 120; Underwound, P.A., Bennett, F.A., A comparison of the biological activities of the cell-adhesive proteins vitronectin and fibronectin (1989) J Cell Sci, 93, pp. 641-649; Hayman, E.G., Pierschbacher, M.D., Suzuki, S., Ruoslahti, E., Vitronectin: A major cell attachment-promoting protein in foetal bovine serum (1985) Exp Cell Res, 160, pp. 245-250; Lopes, Ma., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Lopes, Ma., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Cheng, P., Li, D., Boruvka, L., Rotenberg, Y., Neumann, A.W., Automation of axisymmetric drop shape analysis for measurements of interfacial tensions and contact angles (1990) Colloids Surf, 43, pp. 151-167; Cheng, P., Neumann, A.W., Computational evaluation of axisymmetric drop shape analysis-profile (ADSA-P) (1992) Colloids Surf, 62, pp. 297-306; Saramago, B., Teixeira, M.J., Rosa, M.E., Bordadao, J.C., Influence of the wetting properties of polymeric adhesives on the mechanical behaviour of cork agglomerates (1996) A Adhes Sci Technol, 10, pp. 1111-1127; Voigt, A., Thiel, O., Williams, D., Policova, Z., Zingg, W., Neumann, A.W., Asymmetric drop shape analysis (ADSA) applied to protein solution (1991) Colloid Surf, 58, p. 315; Williams, R.L., Hunt, J.A., Tengvall, P., Fibroblast adhesion onto methyl-silica gradients with and without preadsorbed proteins (1995) J Biomed Mater Res, 29, pp. 1545-1555; Hench, L.L., Ethridge, E.C., (1982) Biomaterials: An Interfacial Approach, , New York: Academic Press; Horbert, T.A., Brash, J.L., Proteins at interfaces. II. Fundamentals and applications (1994) ACS Symposium, 602, pp. 1-23. , Chapter 1, Chapter 7; Vogler, E.A., Interfacial chemistry in biomaterials science (1993) Wettability, 49, pp. 183-250. , Berg JC, editor New York: Marcel Dekker; Chapter 4
Keywords: Adhesion; Adsorption; Algorithms; article; Biocompatible Materials; biomaterial; Biomaterials; Bone; Calcium Compounds; calcium phosphate; Calcium phosphates; Cells; Chemical analysis; Chemistry, Physical; Composite materials; Contact angle; glass; Glass reinforced hydroxyapatite composites; hydrophobicity; hydroxyapatite; Hydroxyapatite-glass composites; Hydroxyapatites; implant; Implants (surgical); Interfacial energy; Phosphorus Compounds; Protein adsorption; Proteins; Surface charge; Surface Properties; surface property; Surface tension; Tricalcium phosphate; Vitronectin; wettability; X-Ray Diffraction; Zeta potential

In vitro growth and differentiation of osteoblast-like human bone marrow cells on glass reinforced hydroxyapatite plasma-sprayed coatings - Ferraz, M.P.; Fernandes, M.H.; Cabral, A.T.; Santos, J.D.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1999)
Human osteoblastic bone marrow cells were cultured far periods of up to 28 days in control conditions and on the surface of a glass reinforced hydroxyapatite composite (HA/G1) and commercial hydroxyapatite (HA) plasma-sprayed coatings, in the 'as-received' condition and after immersion treatment in culture medium for 21 days. Cultures were characterized for total protein content and alkaline phosphatase activity. Scanning electron microscope analyses were performed on control cultures, seeded materials and materials incubated in the absence of cells. Culture media were analyzed for total and ionized calcium and phosphorus concentrations throughout the incubation period. Immersion of HA/G1 and HA coatings in culture medium resulted in significant alterations to the levels of calcium and phosphorus in the medium, leading to surface modifications. However, seeded material samples showed significant differences in the pattern of variation of the levels of these species. Cell proliferation was observed in the 'as-received' HA/G1 composite, but cell mediated formation of mineral deposits was not proved. In contrast, 'as-received' HA hardly supported cell growth. Previously immersed material samples showed cell proliferation and evidence of biological formation of mineral deposits. However, the HA/G1 composite presented better surface characteristics for cell growth as the behavior of bone marrow eel Is was closer to that observed in control cultures.Human osteoblastic bone marrow cells were cultured for periods of up to 28 days in control conditions and on the surface of a glass reinforced hydroxyapatite composite (HA/G1) and commercial hydroxyapatite (HA) plasma-sprayed coatings, in the 'as-received' condition and after immersion treatment in culture medium for 21 days. Cultures were characterized for total protein content and alkaline phosphatase activity. Scanning electron microscope analyses were performed on control cultures, seeded materials and materials incubated in the absence of cells. Culture media were analyzed for total and ionized calcium and phosphorus concentrations throughout the incubation period. Immersion of HA/G1 and HA coatings in culture medium resulted in significant alterations to the levels of calcium and phosphorous in the medium, leading to surface modifications. However, seeded material samples showed significant differences in the pattern of variation of the levels of these species. Cell proliferation was observed in the 'as-received' HA/G1 composite, but cell mediated formation of mineral deposits was not proved. In contrast, 'as-received' HA hardly supported cell growth. Previously immersed material samples cell proliferation and evidence of biological formation of mineral deposits. However, the HA/G1 composite presented better surface characteristics for cell growth as the behavior of bone marrow cells was closer to that observed in control cultures.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1008924516146Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Institute of Biomedical Engineering, Faculties of Dental Medicine, Universidade do Porto, 4200 Porto, PortugalChemicals/CAS: alkaline phosphatase, 9001-78-9; calcium ion, 14127-61-8; hydroxyapatite, 1306-06-5, 51198-94-8; phosphorus, 7723-14-0; protein, 67254-75-5References: Passuti, N., Daculsi, G., Martin, S., (1990) Clinical Implant Materials, p. 255. , edited by V. Soltesz and A. Lee (Elsevier, Amsterdam);Legeros, R., (1988) Adv. Dental Res., 2, p. 164; Hench, L.L., (1992) J. Amer. Ceram. Soc., 74, p. 1487; Kokubo, T., (1993) Bone-Bonding Biomaterals, p. 31. , edited by P. Ducheyne, T. Kokubo and C. A. Blitterswijk (Reed Health-Care Comunications, Leiden, The Netherlands); Daculsi, G., Legeros, R.Z., Henghebaert, M., Barbieux, I., (1990) Calcif. Tissue Int., 46, p. 20; Bagambisa, F.B., Joos, U., Schilli, W., (1993) J. Biomed. Mater. Res., 27, p. 1047; De Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., (1995) J. Biomed. Mater. Res., 29, p. 89; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , JAAS; Raemdonck, W., Ducheyne, P., Meester, P., (1984) Metal and Ceramic Materials, p. 143. , edited by P. Ducheyne and G. W. Hastings (CRC Press, Boca Raton, FL); Rey, C., Freche, M., Heughebaert, M., Vignoles, M., (1991) Bioceramics 4, p. 57. , edited by W. Bonfield, G. W. Hastings and K. E. Tanner (Butterworth-Heinemann, London); Nagase, M., Abe, Y., Udagawa, E., (1992) Biomaterials, 13, p. 172; Burnie, J., Gilchrist, T., (1993) Ceramics in Surgery, p. 169. , edited by P. Vincenzini (Elsevier, Amsterdam); Burnie, F., Gilchrist, T., Ceramics in Surgery, p. 177; Rawlings, R.D., Rogers, P.S., Stokes, P.M., (1987) High Tech Ceramics, p. 73. , edited by P. Vincenzini (Elsevier, Amsterdam); Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Santos, J.D., Lakhan, J.J., Monteiro, F.J., (1995) Biomaterials, 16, p. 521; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., (1995) J. Mater. Sci. Mater. Med., 6, p. 348; Klein, C.P.A.T., Patka, P., Van Der Lubbe, H.B.M., (1991) J. Biomed. Mater. Res., 25, p. 53; Jansen, J.A., Van Der Waerden, J.P.C.M., Wolke, J.G.C., (1993) J. Mater. Sci. Mater. Med., 4, p. 466; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., (1992) J. Biomed. Mater. Res., 26, p. 1365; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., (1994) J. Mater. Sci. Mater. Med., 5, p. 11; Lugscheider, E., Knepper, M., Heimberg, B., Dekker, A., Kirkpatrick, C.J., (1994) J. Mater. Sci. Mater. Med., 5, p. 371; Courteney-Harris, R.G., Kayser, M.V., Downes, S., (1995) Biomaterials, 16, p. 489; Labat, B., Chanson, A., Frey, J., (1995) J. Biomed. Mater. Res., 29, p. 1397; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., (1996) J. Mater. Sci. Mater. Med., 7, p. 21; Anselme, K., Sharrock, P., Hardouin, P., Dard, M., (1997) J. Biomed. Mater. Res., 34, p. 247; Ong, J.L., Prince, C.W., Lucas, L.C., (1995) J. Biomed. Mater. Res., 29, p. 165; Vrouwenvelder, W.C.A., Groot, C.G., De Groot, K., (1995) J. Mater. Sci. Mater. Med., 6, p. 144; Amédée, J., Bareille, R., Jeandot, R., Bordenave, L., Rémy, M., Rouais, F., Baquey, C., (1994) Biomaterials, 15, p. 1029; Maniatopoulos, C., Sodek, J., Melcher, A., (1988) Cell Tissue Res., 254, p. 317; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., (1990) J. Cell Phys., 143, p. 213; Gundle, R., Joyner, C.J., Triffit, J.T., (1995) Bone, 16, p. 597; Fernandes, M.H., Costa, M.A., Carvalho, G.S., (1997) J. Mater. Sci. Mater. Med., 8, p. 61; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., (1997) J. Mater. Sci. Mater. Med., 8, p. 233; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., (1996) J. Mater. Sci. Mater. Med., 7, p. 291; Morais, S., Dias, N., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., (1999) J. Biomed. Mater. Res., 44, p. 176; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., (1991) Bone and Min., 14, p. 27; Ferraz, M.P., Monteiro, F.J., Santos, J.D., J. Biomed. Mater. Res., , submitted; Owen, T.A., Aronow, M., Shalhoub, V., (1990) J. Cell Phys., 143, p. 420; Martin, T.J., Findlay, D.M., Heath, J.K., Ng, K.W., (1993) Handbook of Experimental Pharmacology, p. 149. , edited by J. R. Mundy and T. J. Martin Berlin (Springer-Verlag); Stein, G.S., Lian, J.B., (1993) Cellular and Molecular Biology of Bone, p. 47. , edited by M. Noda (Academic Press, Tokyo); Anderson, H.C., Morris, D.C., (1993) Handbook of Experimental Pharmacology, p. 267. , edited by J. R. Mundy and T. J. Martin Berlin (Springer-Verlag); Gwynn, I.A.P., (1994) J. Mater. Sci. Mater. Med., 5, p. 357; Kirkpatrick, C.J., Wagner, M., Kohler, H., Bittinger, F., Otto, M., Klein, C.L., (1997) J. Mater. Sci. Mater. Med., 8, p. 131; Legeros, R.Z., Orly, I., Gregoire, M., Daculsi, G., (1991) The Bone-Biomaterial Interface, p. 76. , edited by J. E. Davies (University of Toronto Press, Toronto); Chern Lin, J.H., Liu, M.L., Ju, C.P., (1994) J. Biomed. Mater. Res., 28, p. 723; Ghannam, E.L., Ducheyne, P., Spapiro, I., (1995) J. Biomed. Mater. Res., 29, p. 359; Radin, S.R., Ducheyne, P., (1993) J. Biomed. Mater. Res., 27, p. 35; Radin, S.R., Ducheyne, P., (1993) J. Biomed. Mater. Res., 27, p. 1047; Best, S., Sim, B., Kayser, M., Downes, S., (1997) J. Mater. Sci. Mater. Med., 8, p. 97
Keywords: adult; alkaline phosphatase; article; Bone; bone marrow cell; Bone replacement materials; Calcium; calcium ion; case report; Cell culture; cell differentiation; cell growth; Cells; controlled study; culture medium; enzyme activity; Enzyme kinetics; glass; Growth kinetics; human; Human bone marrow cell; human cell; hydroxyapatite; male; osteoblast; Phosphates; phosphorus; priority journal; protein; protein determination; Proteins; scanning electron microscope; Scanning electron microscopy; Sprayed coatings

In vitro osteoblastic differentiation of human bone marrow cells in the presence of metal ions - Morais, S.; Dias, N.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
For periods up to 21 days human bone marrow was cultured in control conditions that favor the proliferation and differentiation of osteoblastic cells. The effect of AISI 316L corrosion products and the corresponding major separate metal ions (Fe, Cr, and Ni) were studied in three different phases of the culture period in order to investigate the effects of metal ions in cell populations representative of osteoblastic cells in different stages of differentiation. Toxicity consequences of the presence of metal ions in bone marrow cultures were evaluated by biochemical parameters (enzymatic reduction of MTT, alkaline phosphatase activity, and total protein content), histochemical assays (identification of ALP-positive cells and Ca and phosphates deposits), and observation of the cultures by light and scanning electron microscopy. Culture media were analyzed for total and ionized Ca and P and also for metal ions (Fe, Cr, and Ni). The presence of AISI 316L corrosion products and Ni salt in bone marrow cultures during the first and second weeks of culture significantly disturbs the normal behavior of these cultures, interfering in the lag phase and exponential phase of cell growth and ALP expression. However, the presence of these species during the third week of culture, when expression of osteoblastic functions occurs (mineralization process), did not result in any detectable effect. Fe salt also disturbs the behavior of bone marrow cell cultures when present during the lag phase and proliferation phase, and a somewhat compromised response between the normal pattern (control cultures) and intense inhibition (AISI 316L corrosion products and Ni salt-added cultures) was observed. Fe did not affect the progression of the mineralization phase. Osteogenic cultures exposed to Cr salt (Cr 3+) presented a pattern similar to the controls, indicating that this element does not interfere, in the concentration studied, in the osteoblastic differentiation of bone marrow cells. Quantification of metal ions in the culture media showed that Cr (originated from AISI 316L corrosion products but from not Cr 3+ salt) and Ni (originated from AISI 316L corrosion products and Ni salt) appear to be retained by the bone marrow cultures. For periods up to 21 days human bone marrow was cultured in control conditions that favor the proliferation and differentiation of osteoblastic cells. The effect of AISI 316L corrosion products and the corresponding major separate metal ions (Fe, Cr, and Ni) were studied in three different phases of the culture period in order to investigate the effects of metal ions in cell populations representative of osteoblastic cells in different stages of differentiation. Toxicity consequences of the presence of metal ions in bone marrow cultures were evaluated by biochemical parameters (enzymatic reduction of MTT, alkaline phosphatase activity, and total protein content), histochemical assays (identification of ALP-positive cells and Ca and phosphates deposits), and observation of the cultures by light and scanning electron microscopy. Culture media were analyzed for total and ionized Ca and P and also for metal ions (Fe, Cr, and Ni). The presence of AISI 316L corrosion products and Ni salt in bone marrow cultures during the first and second weeks of culture significantly disturbs the normal behavior of these cultures, interfering in the lag phase and exponential phase of cell growth and ALP expression. However, the presence of these species during the third week of culture, when expression of osteoblastic functions occurs (mineralization process), did not result in any detectable effect. Fe salt also disturbs the behavior of bone marrow cell cultures when present during the lag phase and proliferation phase, and a somewhat compromised response between the normal pattern (control cultures) and intense inhibition (AISI 316L corrosion products and Ni salt-added cultures) was observed. Fe did not affect the progression of the mineralization phase. Osteogenic cultures exposed to Cr salt (Cr 3+) presented a pattern similar to the controls, indicating that this element does not interfere, in the concentration studied, in the osteoblastic differentiation of bone marrow cells. Quantification of metal ions in the culture media showed that Cr (originated from AISI 316L corrosion products but from not Cr 3+ salt) and Ni (originated from AISI 316L corrosion products and Ni salt) appear to be retained by the bone marrow cultures.
Cited By (since 1996): 35Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(199902)44:2<176::AID-JBM8>3.0.CO;2-6PubMed ID: 10397919Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Universidade do Porto, Rua Dr Manuel Pereira da Silva, 4200 Porto, PortugalChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Alloys; Biocompatible Materials; Calcium, 7440-70-2; Chromium, 7440-47-3; Iron, 7439-89-6; Metals; Nickel, 7440-02-0; Phosphorus, 7723-14-0; Proteins; Stainless Steel, 12597-68-1; Tetrazolium Salts; Thiazoles; thiazolyl blue, 298-93-1References: Williams, D., Cahn, R.W., Bever, M.B., (1990) Concise Encyclopedia of Medical & Dental Materials, pp. 4-70. , Oxford, New York, Beijing, Frankfurt, São Paulo, Sydney, Tokyo, Toronto: Permagon Press;Linden, J.V., Hopler, S.M., Gossling, H.R., Sunderman Jr., F.W., Blood nickel concentrations in patients with stainless-steel hip protheses (1985) Ann Clin Lab Sci, 15, pp. 459-464. , 1985; Weber, G.W., Reid, B.L., Nickel toxicity in young growing mice (1969) J Animal Sci, 28, pp. 620-623; O'Dell, G.D., Miller, W.J., King, W.A., Moore, S.L., Blackmon, D.M., Nickel toxicity in the young bovine (1970) J Nutrition, 100, pp. 1447-1453; Louria, D.B., Joselow, M.M., Browder, A.A., The human toxicity of certain trace elements (1972) Ann Intern Med, 76, pp. 307-319; Whanger, P.D., Effects of dietary nickel on enzyme activities and mineral contents in rats (1973) Toxicol Appl Pharmacol, 25, pp. 323-331; Woodman, J.L., Black, J., Jimenez, S., Organometallic corrosion products of 316L SS and HS-21 in serum: In vitro and in vivo comparison in an acute rat model (1982) Biomaterials 1980, pp. 245-253. , Winter GD, Gibbon DF, Plenk Jr H, editors. Chichester, New York, Brisbone, Toronto, Singapore: John Wiley & Sons; Parfitt, A.M., The physiological and clinical significance of bone histomorphometric data (1983) Bone Histomorphometry: Techniques and Interpretation, pp. 143-223. , Recker RR, editor. Boca Raton, Florida: CRC Press; Jilka, R.L., Manolagas, S.C., The cellular and biochemical basis of bone remodeling (1994) Osteoporosis, pp. 17-48. , Marcus R, editor. Boston: Blackwell Scientific Publications; Owen, M., Lineage of osteogenic cells and their relationship to the stromal system (1985) Bone and Mineral Research, 3, pp. 1-25. , Peck WA, editor. Amsterdam: Elsevier Science Publishers; Owen, T.A., Aronow, M., Shalhoub, V., Progressive development of the rat osteoblast phenotype in vitro: Reciprocal relationships in expression of genes associated with osteoblast proliferation and differentiation during formation of the bone extracellular matrix (1990) J Cell Physiol, 143, pp. 420-430; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionized Ca in osteoblast-like cell culture medium (1996) Electroanalysis, 8 (12), pp. 1174-1178; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9 (10), pp. 791-795; Morais, S., Carvalho, G.S., Sousa, J.P., Chromium determination in osteoblast-like cell culture medium by catalytic cathodic stripping voltammetry with a mercury microelectrode (1998) J Trace Elements Med Biol, 2, pp. 101-108; Morais, S., Carvalho, G.S., Sousa, J.P., Determination of Ni in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with mercury microelectrodes (1997) Electroanalysis, 9 (5), pp. 422-426; Morais, S., Carvalho, G.S., Sousa, J.P., Optimization study for nickel quantification in cell culture medium using mercury film microelectrodes (1996) Portugaliae Electrochimica Acta, 14, pp. 267-272; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tiss Res, 254, pp. 317-330; Berridge, V., Tan, A.S., Characterization of the cellular reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT): Subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch Biochem Biophys, 303, pp. 474-482; Bessey, O., Lowry, O., Breck, M., A method for the rapid determination of alkaline phosphatase with five cubic millileters of serum (1946) J Biol Chem, 164, pp. 321-326; McGee-Russell, M., Histochemical methods for calcium (1958) J Histochem Cytochem, 6, pp. 22-42; Fiske, C.H., Subbarow, Y., The colorimetric determination of phosphorus (1925) J Biol Chem, 66, pp. 373-400; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulate formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 143, pp. 213-221; Gotoh, Y., Hiraiwa, K., Narajama, M., In vitro mineralization of osteoblastic cells derived from human bone (1990) Bone and Miner, 8, pp. 239-250; Cheng, S.L., Yang, J.W., Riffas, L., Zhang, S.F., Avioli, L.V., Differentiation of human bone marrow osteogenic stromal cells in vitro. Induction of the osteoblast phenotype by dexamethasone (1994) Endocrinology, 134, pp. 277-286; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone-derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Arcicla, C.R., Granchi, D.C., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin Mater, 15, pp. 173-190; Gerstenfeld, L.C., Chipman, S.D., Glowacki, J., Lian, J.B., Expression of differential function by mineralizing cultures of chicken osteoblasts (1987) Dev Biol, 122, pp. 46-60; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone and Miner, 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone and Miner, 17, pp. 15-29; Chung, C.H., Golub, E.E., Forbes, E., Tokuoka, T., Shapiro, I.M., Mechanisms of action of β-glycerophosphate on bone cell mineralization (1992) Calcif Tissue Int, 51, pp. 305-311; Boskey, A.L., Stiner, D., Doty, S.B., Binderman, I., Levoy, P., Studies of mineralization in tissue culture: Optimal conditions for cartilage calcification (1992) Bone and Miner, 16, pp. 11-36; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., De Bruijn, J.D., Van Blitterswijk, C.A., Decreased consumption of Ca and P during in vitro biomineralization and biologically induced deposition of Ni and Cr in presence of stainless steel corrosion products (1998) J Biomed Mater Res, 42, pp. 199-212; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralization by osteoblast-like cells. 1. Retardation of tissue mineralization by metal salts (1998) Biomaterials, 19, pp. 13-21; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., De Bruijn, J.D., Van Blitterswijk, C.A., Effects of AISI 316L corrosion products in in vitro bone formation (1998) Biomaterials, 19, pp. 999-1007; Stein, G.S., Lian, J.B., Molecular mechanisms mediating developmental and hormone-regulated expression of genes in osteoblasts: An integrated relationship of cell growth and differentiation (1993) Cellular and Molecular Biology of Bone, pp. 47-95. , Noda M, editor. Tokyo: Academic Press Inc; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., The ultrastructure of the one-hydroxyapatite interface in vitro (1992) J Biomed Mater Res, 26, pp. 1365-1382; Stein, G.S., Lion, J.B., Molecular mechanisms mediated proliferation-differentiation interrelationships during progressive development of the osteoblast phenotype: Update 1995 (1995) Endocrin Rev, 4, pp. 290-297; Abe, Y., Akamine, A., Aida, Y., Maeda, K., Differentiation and mineralization in osteogenic precursor cells derived from fetal rat mandibular bone (1993) Calcif Tissue Int, 52, pp. 365-371; Lomri, A., Tran, M.P.V., Mott, M., Characterization of endosteal osteoblastic cells isolated from mouse caudal vertebrae (1988) Bone, 9, pp. 165-175; McCulloch, C.A.G., Fair, C.A., Tenebaum, H.C., Limeback, H., Homareau, R., Clonal distribution of osteoprogenitor cells in cultured chick peristoa: Functional relationship to bone formation (1990) Dev Biol, 140, pp. 352-361; Sun, Z.L., Wataha, J.C., Hanks, C.T., Effects of metal ions on osteoblast-like cell metabolism and differentiation (1997) J Biomed Mater Res, 34, pp. 29-37; Puleo, D.A., Huh, W.W., Acute toxicity of metal ions in cultures of osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 109-116; Katz, S.A., Salem, H., The toxicology of Cr with respect to its chemical speciation: A review (1993) J Appl Toxicol, 13, pp. 217-224; Anderson, H.C., Morris, D.C., Mineralization (1993) Handbook of Experimental Pharmacology, pp. 267-298. , Mundy GR, Martin TJ, editors. Berlin: Springer-Verlag; Merritt, K., Brown, S.A., Biological effects of corrosion products from metals (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 195-207. , Fraker AC, Griffin CD, editors. ASTM STP 859. Philadelphia: American Society for Testing and Materials; Rae, T., The toxicity of metals used in orthopaedic prostheses (1981) J Bone Joint Surg, 63 B, pp. 435-440; Webb, M., Weinzier, S.M., Uptake of 63Ni 2+ from its complexes with proteins and other ligands by mouse dermal fibroblasts in vitro (1972) Br J Cancer, 26, pp. 292-298; Merritt, K., Wortman, R.S., Millard, M., Brown, S.A., XPS analysis of 316LVM corroded in serum and saline (1983) Biomater Med Devices Artif Organs, 11, pp. 115-124; Bianchi, V., Toso, R.D., Debetto, P., Mechanisms of chromium toxicity in mammalian cell cultures (1980) Toxicology, 17, pp. 219-224; Lucas, L.C., Bearden, L.J., Lemons, J.E., Ultrastructural examination of in vitro and in vivo cells exposed to elements from type 316L stainless steel (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 208-222. , Fraker AC, Griffin CD, editors. ASTM STP 859. Philadelphia: American Society for Testing and Materials
Keywords: alkaline phosphatase; Alloys; article; Batch cell culture; Biocompatible Materials; biotechnology; Bone; Bone cells; bone marrow cell; Bone Marrow Cells; bone mineralization; bone prosthesis; Calcium; Cell culture; cell differentiation; Cell Division; cell population; Cells, Cultured; Chromium; controlled study; Corrosion; Corrosion products; Cytotoxicity; Differentiation; human; human cell; Human osteoblast-like cells; Humans; Implants (surgical); Ions; Iron; joint prosthesis; materials testing; metal ion; Metal ions; Metals; Nickel; osteoblast; Osteoblasts; phosphorus; Prostheses and Implants; Proteins; Stainless steel; Steel corrosion; Tetrazolium Salts; Thiazoles

Individual study of chromium in the stainless steel implants degradation: An experimental study in mice - Pereira, M.D.C.; Pereira, M.D.L.; Sousa, J.P. (BioMetalsBioMetals, 1999)
To study the accumulation and the histological effects in mice organs caused by hexavalent chromium, one of the corrosion products released from AISI 316L stainless steel implants, mice groups were subcutaneously injected with a metallic solution of chromium during a certain period of time. Similar injections were made with HBSS (Hank's Balanced Salt Solution) in other groups to be used as controls. The levels of chromium found in the liver, kidney and spleen of the control and the treated animals were obtained by atomic absorption spectrometry (AAS) and were compared to those obtained by AdSV (adsorptive stripping voltammetry) to test the accuracy of the results. During the experimental period, the liver and spleen showed a progressive and significant accumulation of chromium whereas in the kidney the significant accumulation found after the first week practically remained unchanged during the four weeks. Apparently, the histological analysis of these tissues did not evidence any relevant morphological alteration induced by the chromium accumulations during the four weeks of treatment.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: BOMEEPubMed ID: 10581692Language of Original Document: EnglishCorrespondence Address: Do Carmo Pereira, M.; Departamento de Engenharia Quimica, FEUP, Rua dos Bragas, 4050-123 Porto, Portugal; email: mcsp@fe.up.ptChemicals/CAS: Biocompatible Materials; Chromium, 7440-47-3; Stainless Steel, 12597-68-1References: Bartolozzi, A., Black, J., Chromium concentrations in serum, blood clot and urine from patients following total hip arthroplasty (1985) Biomaterials, 6, pp. 2-8;Black, J., Maitin, E.C., Gelman, H., Morris, D.M., Serum concentrations of chromium, cobalt and nickel after total hip replacement: A six month study (1983) Biomaterials, 4, pp. 160-164; Brien, W.W., Salvati, E.A., Healey, J.H., Bansal, M., Ghelman, B., Betts, F., Osteogenic sarcoma arising in the area of a total hip replacement (1990) J Bone Joint Surg, 72 A, pp. 1097-1099; Brown, S.A., Farnsworth, U., Merritt, K., Crowe, T.D., In vitro and in vivo metal ion release (1988) J Biomed Mater Res, 22, pp. 321-338; Brown, S.A., Zhang, K., Merritt, K., Payer, J.H., In vivo transport and excretion of corrosion products from accelerated anodic corrosion of porous coaled 1-75 alloy (1993) J Biomed Mater Res, 27, pp. 1007-1017; Burrows, D., (1983) Chromium: Metabolism and Toxicity, , CRC Press, Boca Raton, Florida; Dobbs, H.S., Minski, M.J., Metal ion release after total hip replacement (1980) Biomaterials, 1, pp. 193-198; Kargacin, B., Squibb, K.S., Cosentino, S., Zhitkovich, A., Costa, M., Comparison of the uptake and distribution of chromate in rats and mice (1993) Biol Trace Element Res, 36, pp. 307-318; Katz, S.A., Salem, H., The toxicology of chromium with respect to its chemical speciation: A review (1993) J Appl Toxicol, 13, pp. 217-224; Katz, S.A., Salem, H., (1994) The Biological and Environmental Chemistry of Chromium, , VCH Publishers; Langard, S., Hensten-Pettersen, A., Chromium toxicology (1981) Systemic Aspects of Biocompatibility, p. 143. , Williams DF. eds. Boca Raton, Florida, CRC Press; Martin, A., Bauer, T.W., Manley, M.T., Marks, K.E., Osteosarcoma at the site of total hip replacement (1988) J Bone Joint Surg, 70 A, pp. 1561-1566; Merritt, K., Brown, S.A., Biological effects of corrosion products from metals (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 195-207. , Fraker AC. Griffin CD. eds. Philadelphia, American Society for Testing and Materials; Merritt, K., Brown, S.A., Release of hexavalent chromium from corrosion of stainless steel and cobalt-chromium alloys (1995) J Biomed Mater Res, 29, pp. 627-633; Merritt, K., Brown, S.A., Sharkey, N.A., Blood distribution of nickel, cobalt, and chromium following intramuscular injection into hamsters (1984) J Biomed Mater Res, 18, pp. 991-1004; Merritt, K., Brown, S.A., Sharkey, N.A., The binding of metal salts and corrosion products to cells and proteins in vitro (1984) J Biomed Mater Res, 18, pp. 1005-1015; Merritt, K., Crowe, T.D., Brown, S.A., Elimination of nickel, cobalt, and chromium following repeated injections of high dose metal salts (1989) J Biomed Mater Res, 23, pp. 845-862; Merritt, K., Fedele, C.D., Brown, S.A., Chromium 6+ or 3+ release during corrosion; And in vivo distribution (1992) Biomaterial- Tissue Interfaces, Advances in Biomaterials, 10, pp. 49-53. , Doherty PJ. et al., eds; Pereira, M.C., Faria, J.L., Reis, M.L., Sousa, J.P., Nickel quantification in mice organs by adsorptive cathodic stripping voltammetry using microelectrodes (1997) Electroanalysis, 9, pp. 150-154; Pereira, M.C., Pereira, M.L., Sousa, J.P., Adsorptive stripping voltammetric measurements of chromium accumulation in mice organs using mercury film microelectrodes (1997) Electroanalysis, 9, pp. 941-944; Pereira, M.C., Pereira, M.L., Sousa, J.P., Evaluation of nickel toxicity on liver, spleen and kidney of mice after administration of high-dose metal ion (1998) J Biomed Mater Res, 40, pp. 40-47; Pereira, M.C., Pereira, M.L., Sousa, J.P., Adsorptive stripping measurements of iron accumulation in mice kidney using microlectrodes and histological features (1998) J Trace Elements Med Biol, 12, pp. 50-55; Pohler, O.E.M., Degradation of metallic orthopedic implants (1983) Biomaterials in Reconstructive Surgery, pp. 158-228. , Rubin LR, ed. The C. V. Mosby Company; Ross, M.H., Rowrell, L.J., (1985) Histology a Text and Atlas, , Williams & Wilkins; Smith, G.K., Black, J., Estimation of in vivo type 316L stainless steel corrosion rate from blood transport and organ accumulation data (1985) Corrosion and Degradation of Implant Materials; Second Symposium, pp. 223-247. , Fraker AC, Griffin CD, eds. American Philadelphia, Society for Testing and Materials; Sunderman F.W., Jr., Hopfer, S.M., Swift, T., Cohalt, chromium, and nickel concentrations in body fluids of patients with porous-coated knee or hip prostheses (1989) J Orthop Res, 7, pp. 307-315; Yang, J., Black, J., Competitive binding of chromium, cobalt and nickel to serum proteins (1994) Biomaterials, 15, pp. 262-268; Young, E., Houwing, R.H., Patch test results with standard allergens over a decade (1987) Contact Dermatitis, 17, pp. 104-107
Keywords: animal experiment; animal tissue; Animalia; Animals; article; atomic absorption spectrometry; Biocompatible Materials; biomaterial; body weight; Chromium; controlled study; Corrosion; histology; histopathology; implant; Injections, Subcutaneous; Kidney; Liver; liver level; male; Mice; Mice organs; Mice, Inbred Strains; mouse; nonhuman; potentiometry; Prostheses and Implants; Spleen; Stainless steel; tissue distribution

Adhesion and microstructural characterization of plasma-sprayed hydroxyapatite/glass ceramic coatings onto Ti-6Al-4V substrates - Silva, P.L.; Santos, J.D.; Monteiro, F.J.; Knowles, J.C. (Surface and Coatings TechnologySurf. Coat. Technol., 1998)
Commercial hydroxyapatite (HA), Ca 10(PO 4) 6(OH) 2, powders were reinforced with 4% of a CaO-P 2O 5 based glass during its sintering process. Double layered coatings were obtained by Plasma Spraying and composed of 50 μm commercial HA, followed by a 50 μm (HA)/P 2O 5-CaO based glass composite coating. Samples were characterized by X-ray diffraction (XRD) analysis and it was shown that they were constituted of an HA matrix with small traces of tricalcium phosphate (β-TCP) phase. The XRD spectra were quite similar to those of commercial HA coatings. For coating to substrate adhesion two different tests were performed: adhesion tests according to ASTM C 633-79 and ASTM D 1002-83 standards. Higher values were obtained for ASTM C 633-79 than for ASTM D 1002-83, 35 and 15 MPa, respectively. This behavior is discussed in terms of the different stress effort applied to specimens. The results obtained with ASTM C 633-79 show that these double layered satisfy the stress requirements for load bearing biomedical applications. © 1998 Published by Elsevier Science S.A.
Cited By (since 1996): 41Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Silva, P.L.; INEB-Inst. de Engenharia Biomedica, Praça Coronel Pacheco 1, 4050 Porto, PortugalReferences: Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, p. 165. , Takayama Press System Center, JAAS, Tokyo;Barney, V.C., Levin, M.P., Adams, D.F., (1986) J. Periodont., 57, p. 764; Ducheyne, P., (1987) J. Biomed. Mater. Res. Appl. Biomater., 21, p. 219; Legeros, R.Z., (1988) Adv. Dent. Res., 2, p. 164; Williams, D., (1986) Medical and Dental Materials, , Pergamon Press; Akao, M., Haoki, K., Kato, (1981) J. Mater. Sci., 16, p. 809; With, G., Van Dijk, H., Hattu, N., Prijs, K., (1981) J. Mater. Sci., 16, p. 1592; Santos, J.D., Silva, P.L., Knowles, J.C., Monteiro, F.J., (1996) J. Mater. Sci. Mater. Med., 7, p. 187; Rey, C., (1990) Biomateriais, 11, p. 14; Evans, G., Behiri, J., Currey, J., Bonfield, B., (1990) J. Mater. Sci. Mater. Med., 1, p. 38; Matejka, D., Benko, B., (1989) Plasma Spraying of Metallic Materials, , Wiley, New York; Brown, S.D., (1984) Thin Sol. Films, 119, p. 127; Mittal, K.L., Adhesion Measurement of Thin Films, Thick Films and Bulk Coatings, , ASTM STP 840; ASTM D 1002, standard test method for strength properties of adhesive in shear by tension loading (1983) Annual Book of ASTM Standards; ASTM C 633-79, standard test method for adhesion or cohesive strength of flame sprayed coatings (1979) Annual Book of ASTM Standards Section 2; Ruiz, J., González, J.A., (1984) Rev. Metal., 20 (1). , Madrid
Keywords: Adhesion; Ceramic coatings; Characterization; coating; Hydroxyapatite glass ceramic coatings; materials testing; Mechanical properties; Microstructure; Phosphates; Plasma spraying; Stresses; Titanium aluminum vanadium substrates; X ray diffraction analysis; X-Ray Diffraction

Adsorptive stripping measurements of iron accumulation in mice kidney using microelectrodes and histological features - Pereira, M.C.; Pereira, M.L.; Sousa, J.P. (Journal of Trace Elements in Medicine and BiologyJ. Trace Elem. Med. Biol., 1998)
The toxic effects caused by iron in kidney was performed on experimental studies with mice following administration of a metallic solution of this specie to simulate the iron corrosion products of a metallic implant. To quantify the total levels of iron present in this organ, an electrochemical method was chosen based on the application of square wave voltammetry using adsorptive collection of iron-catechol on a mercury film microelectrode (MFM). The optimal working conditions to produce a very stable and reproducible iron peak in the digested kidney samples were found to be pH=7.2 provided by 8.0 mmol/L PIPES buffer, catechol concentration of 3.0x10
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: JTEBFPubMed ID: 9638613Language of Original Document: EnglishCorrespondence Address: Sousa, J.P.; INEB-Inst. de Engenharia Biomedica, Departamento de Engenharia Quimica, Faculdade Engenharia Univ. do Porto, Praca do Coronel Pacheco, 1, 4050 Porto, PortugalChemicals/CAS: Iron, 7439-89-6; Mercury, 7439-97-6References: Traisnel, M., Le Maguer, D., Hildebrand, H.F., Iost, A., Corrosion of surgical implants (1990) Clin. Mater., 5, pp. 309-318;Sutow, E.J., Pollack, S.R., The biocompatibility of certain stainless steels (1981) Biocompatibility of Clinical Implant Materials, 1, pp. 77-98. , Williams, D.F. eds CRC Press, Boca Raton, Florida; Ferguson Jr., A.B., Laing, P.G., Hodge, E.S., The ionization of metal implants in living tissues (1960) J. Bone Joint Surg., 42 A, pp. 77-90; Winter, G.D., Wear and corrosion products in tissues and the reactions they provoke (1976) Biocompatibility of Implant Materials, pp. 28-54. , Williams, D.F. eds London; Lux, F., Zeisler, R., Investigations of the corrosive deposition of components of metal implants and the behaviour of biological trace elements in metallosis tissue by means of instrumental multi-element activation analysis (1974) J. Radioanal. Chem., 19, pp. 289-297; Merritt, K., Brown, S.A., Sharkey, N.A., Blood distribution of nickel, cobalt, and chromium following intramuscular injection into hamsters (1984) J. Biomed. Mater. Res., 18, pp. 991-1004; Merritt, K., Brown, S.A., Biological effects of corrosion products from metals (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 195-207. , Fraker, A.C., Griffin, C.D. eds American Society for Testing and Materials, Philadelphia; K. Merritt, K.A., Brown, S.A., Metal sensitivity reactions to bone screws in rabbits (1982) Clinical Applications of Biomaterials, pp. 85-93. , John Wiley & Sons Ltd; Woodman, J.L., Black, J., Jimenez, S., Organometallic corrosion products of 316L SS HS-21 in serum: In vitro and in vivo comparison in an acute rat model (1982) Biomaterials 1980, pp. 245-250. , Winter, G.D., Gibbons, D.F., Plenk, Jr., H. John Wiley & Sons Ltd; Merritt, K., Crowe, T.D., Brown, S.A., Elimination of nickel, cobalt, and chromium following repeated injections of high dose metal salts (1989) J. Biomed. Mater. Res., 23, pp. 845-862; Pereira, M.L., Pereira, M.C., Sousa, J.P., Evaluation of nickel effects on mouse liver: Tissue response and metal ion accumulation (1995) Biomedical Letters, 52, pp. 235-244; Pereira, M.C., Pereira, M.L., Sousa, J.P., Evaluation of nickel toxicity on liver, spleen and kidney of mice after administration of high-dose metal ion (1997) J. Biomed. Mater Res., pp. XXXXXX. , in press; Schafer, B.A.I., Cheron, R.G., Dluhy, R., Cooper, B., Gleason, R.E., Soeldner, J.S., Bunn, H.F., Clinical consequences of acquired transfusional iron overload in adults (1981) N Engl. J. Med., 304, p. 319; Black, J., Mineral metabolism (1981) Biological Performance of Materials: Fundamentals of Biocompatibility. Biomedical Engineerins and Instrumentation Series, pp. 158-168. , Plonsey R., Katz, J.L. Marcel Dekker; Bernat, I., Iron deficiency (1983) Iron Metabolism, pp. 215-274. , Plenum Press, New York; Nakamura, K., Watanabe, H., Orii, H., Direct measurement of iron in serum by electrothermal atomic absorption spectrometry (1980) Anal. Chim. Acta., 108, pp. 67-71; Van Beek, H., Greefkes, H.C.A., Baars, A.J., Determination of copper, iron, manganese, lead and cadmium in automatically wet-digested animal tissue by graphite-furnace atomic absorption spectrometry with Zeeman background correction (1993) Talanta., 34, pp. 580-582; Van Wyck, D.B., Schifman, R.B., Stivelman, J.C., Ruiz, J., Martin, D., Rapide sample preparation for determination of iron in tissue by closed-vessel digestion and microwave energy (1988) Clin. Chem., 34 (6), pp. 1128-1130; Chakraborti, D., Burguera, M., Burguera, J.L., Analysis of standard reference materials after microwave-oven digestion in open vessels using graphite furnace atomic absorption spectrophotometry and Zeeman-effect background correction (1993) Fresenius J. Anal. Chem., 347, pp. 233-237; Lugowski, S., Smith, D.C., Van Loon, J.C., The determination of At, Cr, Co, Fe, and Ni in whole blood by electrothermal atomic absorption spectrophotometry (1987) J. Biomed. Mater. Res., 21, pp. 657-674; Wightman, R.M., Microvoltammetric electrodes (1981) Anal. Chem., 53, pp. 1125A-1134A; Pletcher, D., Why microelectrodes? (1991) Microelectrodes: Theory and Applications, pp. 3-16. , Montenegro, M.I., Queirós, M.A., Daschbach, J.L eds NATO-ASI, Kluwer Academic Publishers, the Netherlands; Wojciechowski, M., Go, W., Osteryoung, J., Square-wave anodic stripping analysis in the presence of dissolved oxygen (1984) Anal. Chem., 57, pp. 155-158; Kalvoda, R., Kopanica, M., (1989) Pure & Appl. Chem., 61, pp. 97-112; Wang, J., Principles (1985) Stripping Analysis, pp. 9-64. , VCH publishers, Inc; Perejra, M.C., Faria, J.L., Reis, M.L., Sousa, J.P., Nickel quantification in mice organs by adsorptive cathodic stripping voltammetry using mercury microelectrodes (1996) Electroanalysis, 9, pp. 150-154; Van Den Berg, C.M.G., Huang, Z.Q., Determination of iron in seawater using cathodic stripping voltammetry preceded by adsorptive collection with the hanging mercury drop electrode (1984) J. Electroanal. Chem., 177, pp. 269-280; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell cultures medium by adsorptive cathodic stripping voltammetry with mercury microelectrodes (1997) Electroanalysis, 9; Wang, J., Mannino, S., Application of adsorptive stripping voltammetry to the speciation and determination of iron (III) and total iron in wines (1989) Analyst, 114, pp. 643-645; Smith, G.K., Black, J., Estimation of in vivo type 316L stainless steel corrosion rate from blood transport and organ accumulation data (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 223-247. , Fraker, A.C. and Griffin. Eds. American Society for Testing Materials; Pereira, M.C., Sousa, J.P., Determination of total iron in biological sample solutions with mercury microelectrodes (1996) Portugaliae Electrochimica Acta, 14, pp. 273-278; Pereira, M.C., Pereira, M.L., Sousa, J.P., Adsorptive stripping voltammetric measurements of chromium accumulation in mice organs using mercury microelectrodes (1997) Electroanalysis, 9, pp. 941-944
Keywords: , biomaterials; Adsorptive stripping; animal experiment; animal model; animal tissue; Animals; article; atomic absorption spectrometry; biomaterial; controlled study; electrochemical analysis; electrochemistry; histology; Iron; iron absorption; Kidney; male; Mercury; metal implantation; Mice; microelectrode; Microelectrodes; mouse; nonhuman; potentiometry; priority journal; Toxicology

Chromium determination in osteoblast-like cell culture medium by catalytic cathodic stripping voltammetry with a mercury microelectrode - Morais, S.; De Carvalho, G.S.; Sousa, J.P. (Journal of Trace Elements in Medicine and BiologyJ. Trace Elem. Med. Biol., 1998)
A catalytic cathodic stripping voltammetric procedure for the determination of total chromium in osteoblast-like cell culture medium using a mercury film microelectrode (MFM) was optimised. The method is based on the pre-concentration of the Cr(III)-diethylenetriaminepentaacetic acid (DTPA) complex by adsorption at the potential of -1.00 V (vs. Ag/AgCl) in the presence of 10 x 10
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: JTEBFPubMed ID: 9760419Language of Original Document: EnglishCorrespondence Address: Morais, S.; Inst. Engenharia Biomedica (INEB), Praca Coronel Pacheo 1, 4050 Porto, PortugalChemicals/CAS: Acetates; Chromium, 7440-47-3; Culture Media; Mercury, 7439-97-6; NitratesReferences: Ferguson Jr., A.B., Laing, P.G., Hodge, E.S., The ionization of metal implants in living tissues (1960) J. Bone Joint Surg., 42 A, pp. 77-90;Ferguson Jr., A.B., Akahoshi, Y., Laing, P.G., Hodge, E.S., Trace metal ion concentration in the liver, kidney, spleen and lung of normal rabbits (1962) J Bone Joint Surg., 44 A, pp. 317-322; Ferguson Jr., A.B., Akahoshi, Y., Laing, P.G., Hodge, E.S., Characteristics of trace ions released from embedded metal implants in the rabbit (1962) J. Bone Joint Surg. 1962, 44 A, pp. 323-336; Lux, F., Ziesler, R., Investigations of the corrosive deposition of components of metal implants and of the behaviour of biological trace elements in metallosis tissue by means of instrumental multi-elemental activation analysis (1974) J. Radioanal. Chem., 19, pp. 289-297; Smith, G.K., Black, J., Estimation of in vivo type 316L stainless steel corrosion rate from blood transport and organ accumulation data (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 223-247. , ASTM STP 859 (Fraker, A. C. and Griffin, C. D. ,Eds.). American Society for Testing and Materials, Philadelphia; Minski, M.J., Dobbs, H.S., (1980) Trace Element Analytical Chemistry in Medicine and Biology, pp. 339-350. , Bratter, P., Schramel, P., Eds., Walter de Gruyter, Berlin; Smith, G.K., (1982) Systemic Transport and Distribution of Iron and Chromium from 316L Stainless Steel Implants, , Ph.D. Thesis, University of Pennsylvania, Philadelphia; Brown, S.A., Farnsworth, L.J., Merritt, K., Crowe, T.D., In vitro and in vivo metal ion release (1988) J. Biomed. Materials Research, 22, pp. 321-338; Lucas, L.C., Bearden, L.J., Lemons, J.E., Ultrastructural examination of in vitro and in vivo cells exposed to elements from type 316L stainless steel (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 208-222. , ASTM STP 859 (Fraker, A. C. and Griffin, C. D., Eds.), American Society for Testing and Materials, Philadelphia; Merritt, K., Brown, S.A., Biological effects of corrosion products from metals (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 195-207. , ASTM STP859 (Fraker, A. C. and Griffin, C. D., Eds.), American Society for Testing and Materials, Philadelphia; Smith, G.K., Black, J., Models for systemic effects of metallic implants (1977) NBS Special Publication 472, pp. 23-28. , Weinstein, A., Eds., U. S. Government Printing Office, Washington D. C; Deutman, R., Mulder, T.J., Brian, R., Nater, J.P., Metal sensitivity before and after total hip arthroplasty (1977) J. Bone Jt. Surg., 59 A, pp. 862-865; Crosmun, S.T., Mueller, T.R., The determination of chromium (VI) in natural waters by differential pulse polarography (1975) Anal. Chim. Acta, 75, pp. 199-205; Golimowski, J., Valenta, P., Nurnberg, H.W., Trace determination of chromium in various water types by adsorption differential pulse polarography (1985) Fresenius Z. Anal. Chem., 322, pp. 315-322; Boussemart, M., Van Den Berg, C.M.G., Ghaddaf, M., The determination of the chromium speciation in sea water using catalytic cathodic stripping voltammetry (1992) Anal. Chim. Acta, 262, pp. 103-115; Paneli, M., Voulgaropoulos, A.V., Kalcher, K., The catalytic adsorptive stripping voltammetry determination of chromium with TTHA and nitrate (1993) Mikrochim. Acta, 110, pp. 205-215; Wang, J., Lu, J.A., Olsen, K., Measurement of ultratrace levels of chromium by adsorptive-catalytic stripping voltammetry in the presence of cupferron (1992) Analyst, 117, pp. 1913-1917; Nurnberg, H.W., Studies on toxic trace metals in the environment by advanced polarographic methods (1978) Proc. Analyt. Div. Chem. Soc., 15, pp. 275-283; Ottaway, J.M., Fell, G.S., Determination of chromium in biological materials (1986) Pure and Applied Chemistry, 58, pp. 1707-1720; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9, pp. 791-795; Morais, S., Carvalho, G.S., Sousa, J.P., Determination of nickel in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9, pp. 422-426; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionised calcium in osteoblast-like cell culture medium (1996) Electroanalysis, 8, pp. 1174-1178; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralisation by osteoblast-like cells: Part I- Retardation of tissue mineralisation by metal salts (1998) Biomaterials, 19, pp. 13-21; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., Bruijn, J.D., Van Blitterswijk, C.A., Decreased consumption of Ca and P during in vitro biomineralisation and biologically-induced deposition of Ni and Cr in the presence of stainless steel corrosion products (1998) J. Biomed. Mater. Res., , in press; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro osteoblastic differentiation of human bone marrow cells in the presence of metal ions (1998) J. Biomed. Mater. Res., , in press; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res., 254, pp. 317-330; Kotz, L., Henze, G., Kaiser, G., Pahlke, S., Veber, M., Tolg, G., Wet mineralisation of organic matrices in glassy carbon vessels in a pressure-bomb system for trace element analysis (1979) Talanta, 26, pp. 681-691; Peng, J., Jin, W., Anodic stripping voltammetric determination of trace lead in micro-samples with a mercury-ultramicroelectrode (1992) Anal. Chim. Acta, 264, pp. 213-219; Wehmeyer, K.R., Wightman, R.M., Cyclic voltammetry and anodic stripping voltammetry with mercury ultramicroelectrodes (1985) Anal. Chem., 57, pp. 1989-1993; Wightman, R.M., Wiptd, O., Voltammetry at ultramicroelectrodes (1989) Electroanalytical Chemistry, 15, pp. 335-336. , Bard, A. J., Ed., Marcel, Dekker, New York; Wurfels, M., Jackwerth, E., Stoeppler, M., Residues from biological materials after pressure decomposition with nitric acid Part 3 a (1989) Anal. Chim. Acta, 226, pp. 31-41; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralisation by osteoblast-like cells: Part II- Characterisation of cellular culture supernatants (1998) Biomaterials, 19, pp. 23-29; Wurfels, M., Jackwerth, E., Stoeppler, M., Residues from biological materials after pressure decomposition with nitric acid Part 2 a (1989) Anal. Chim. Acta, 226, pp. 17-30; Gilbert, T.R., Clay, A.M., Determination of chromium in sea water by atomic absorption spectrometry (1973) Anal. Chim. Acta, 67, pp. 289-295; Ping, L., Matsumoto, K., Fuwa, K., Determination of urinary chromium levels for healthy men and diabetic patients by electric thermal atomic absorption spectrometry (1983) Anal. Chim. Acta, 147, pp. 205-212; Torrance, K., Gatford, C., Determination of soluble chromium in simulated PWR coolant by differential-pulse adsorptive stripping voltammetry (1987) Talanta, 34, pp. 939-944; Lanza, P., Taddia, M., The differential pulse polarographic determination of chromium in gallium arsenide (1984) Anal. Chim. Acta, 157, pp. 37-44; Miller, J.N., Basic statistical methods for analytical chemistry. Part 2: Calibration and regression (1991) Analyst, 116, pp. 3-14; Ringbom, A., (1963) Complexation in Analytical Chemistry, pp. 332-333. , Elving, P. J. and Kolthoff, I. M., Eds, Interscience Publishers, New York/London; Black, J., Maitin, E.C., Gelman, H., Morris, D.M., Serum concentrations of Cr, Co, and Ni after total hip replacement: A six months study (1983) Biomaterials, 4, pp. 160-164; Bartolozzi, A., Black, J., Chromium concentrations in serum, blood clot and urine from patients following total hip arthroplasty (1985) Biomaterials, 6, pp. 2-8; Dobbs, H.S., Minski, J., Metal ion release after total hip replacement (1980) Biomaterials, 1, pp. 193-198; Katz, S., Salem, H., The toxicology of chromium with respect to its speciation: A review (1993) J. Applied Toxicology, 13, pp. 217-224; Bianchi, V., Toso, R.D., Debetto, P., Mechanisms of chromium toxicity in mammalian cell cultures (1980) Toxicology, 17, pp. 219-224; Hopkins, L.L., Schwartz, K., Chromium (III) binding to serum proteins, specifically siderophilin (1964) Biochem. Biophys. Acta, 90, pp. 484-491; Nurnberg, H.W., The voltammetric approach in trace metal chemistry of natural waters and atmospheric precipitation (1984) Anal. Chim. Acta, 164, pp. 1-21
Keywords: Acetates; animal cell; Animalia; Animals; article; atomic absorption spectrometry; Bone Marrow Cells; catalysis; Cell culture; Cells, Cultured; Chromium; complex formation; controlled study; Culture Media; culture medium; drug determination; electrochemistry; Electrodes; Hydrogen-Ion Concentration; in vitro study; Kinetics; Mercury; microelectrode; Microelectrodes; Nitrates; nonhuman; osteoblast; Osteoblasts; potentiometry; priority journal; Rabbits; Reproducibility of Results; sensitivity and specificity; Stromal Cells; technique

Decreased consumption of Ca and P during in vitro biomineralization and biologically induced deposition of Ni and Cr in presence of stainless steel corrosion products - Morais, S.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S.; De Bruijn, J.D.; Van Blitterswijk, C.A. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1998)
The purpose of this study was to investigate the effects of 316L stainless steel (SS) corrosion products on the in vitro biomineralization process, because tissue necrosis, bone loss, impaired bone mineralization, and loosening of orthopedic implants are associated with ions and debris resulting from biodegradation. Rat bone marrow cells were cultured in experimental conditions that favored the proliferation and differentiation of osteoblastic cells and were exposed to SS corrosion products obtained by electrochemical means for periods ranging from 1 to 21 days. Quantification of total and ionized Ca and P, as well as Fe, Cr, and Ni, ions in the culture media of control and metal added cultures during the incubation period was performed to study the influence of corrosion products on the Ca and P consumption that occurs during the mineralization process. Control cultures and metal effects on cultures were evaluated concerning DNA content, enzymatic reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), and alkaline phosphatase (ALP) activity. Histochemical detection of ALP, Ca, and phosphate deposition, and examination of the cultures by scanning and transmission electron microscopy (SEM and TEM) were also performed. The presence of SS corrosion products resulted in impairment of the normal behavior of rat bone marrow cultures. Levels of Cr and Ni in the medium of cultures exposed to 316L SS corrosion products decreased throughout the incubation period, suggesting a regular deposition of these species; these results were supported by TEM observation of the cultures. Cultures exposed to the corrosion products presented lower DNA content, MTT reduction, and ALP activity and failed to form mineralized areas. These cultures showed negative staining on histochemical reactions for the identification of calcium and phosphate deposition and SEM and TEM examination did not show mineral globular structures or mineralization foci, respectively, which is characteristic of cultures grown in control conditions. These results suggest that metal ions associated with 316L SS are toxic to osteogenic cells, affecting their proliferation and differentiation.The purpose of this study was to investigate the effects of 316L stainless steel (SS) corrosion products on the in vitro biomineralization process, because tissue necrosis, bone loss, impaired bone mineralization, and loosening of orthopedic implants are associated with ions and debris resulting from biodegradation. Rat bone marrow cells were cultured in experimental conditions that favored the proliferation and differentiation of osteoblastic cells and were exposed to SS corrosion products obtained by electrochemical means for periods ranging from 1 to 21 days. Quantification of total and ionized Ca and P, as well as Fe, Cr, and Ni, ions in the culture media of control and metal added cultures during the incubation period was performed to study the influence of corrosion products on the Ca and P consumption that occurs during the mineralization process. Control cultures and metal effects on cultures were evaluated concerning DNA content, enzymatic reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), and alkaline phosphatase (ALP) activity. Histochemical detection of ALP, Ca, and phosphate deposition, and examination of the cultures by scanning and transmission electron microscopy (SEM and TEM) were also performed. The presence of SS corrosion products resulted in impairment of the normal behavior of rat bone marrow cultures. Levels of Cr and Ni in the medium of cultures exposed to 316L SS corrosion products decreased throughout the incubation period, suggesting a regular deposition of these species; these results were supported by TEM observation of the cultures. Cultures exposed to the corrosion products presented lower DNA content, MTT reduction, and ALP activity and failed to form mineralized areas. These cultures showed negative staining on histochemical reactions for the identification of calcium and phosphate deposition and SEM and TEM examination did not show mineral globular structures or mineralization foci, respectively, which is characteristic of cultures grown in control conditions. These results suggest that metal ions associated with 316L SS are toxic to osteogenic cells, affecting their proliferation and differentiation.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(199811)42:2<199::AID-JBM5>3.0.CO;2-KPubMed ID: 9773816Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Universidade do Porto, Rua Manuel Pereira da Silva, 4200 Porto, PortugalChemicals/CAS: Biocompatible Materials; Calcium, 7440-70-2; Chromium, 7440-47-3; Nickel, 7440-02-0; Phosphorus, 7723-14-0; Steel, 12597-69-2References: Ferguson Jr., B., Akahoshi, Y., Laing, P.G., Hodge, E.S., Trace metal ion concentration in the liver, kidney, spleen and lung of normal rabbits (1962) J. Bone Joint Surg., 44 A, pp. 317-322;Ferguson Jr., A.B., Akahoshi, Y., Laing, P.G., Hodge, E.S., Characteristics of trace ions released from embedded metal implants in the rabbit (1962) J. Bone Joint Surg., 44 A, pp. 323-336; Ferguson Jr., A.B., Laing, P.G., Hodge, E.S., The ionization of metal implants in living tissues (1960) J. Bone Joint Surg., 42 A, pp. 77-90; Lux, F., Ziesler, R., Investigations of the corrosive deposition of components of metal implants and of the behavior of biological trace elements in metallosis tissue by means of instrumental multi-elemental activation analysis (1974) J. Radioanal. Chem., 19, pp. 289-297; Smith, G.K., Black, J., Estimation of in vivo type 316L stainless steel corrosion rate from blood transport and organ accumulation data (1985) Corrosion and Degradation of Implant Materials: Second Symposium, ASTM STP 859, pp. 223-247. , A. C. Fraker and C. D. Griffin (eds.), American Society for Testing and Materials, Philadelphia, Pennsylvania; Merritt, K., Brown, S.A., Biological effects of corrosion products from metals (1985) Corrosion and Degradation of Implant Materials: Second Symposium, ASTM STP 859, pp. 195-207. , A. C. Fraker and C. D. Griffin, (eds.), American Society for Testing and Materials, Philadelphia, Pennsylvania; Smith, G.K., Black, J., Models for systemic effects of corrosion products (1977) Retrieval and Analysis of Orthopedics Implants, pp. 23-28. , A. Weinstein D. Gibbons, S. A. Brown, and A. W. Ruff (eds.), NBS Special Publication 472, U.S. Government Printing Office, Washington, D.C; Deutman, R., Mulder, T.J., Brian, R., Nater, J.P., Metal sensitivity before and after total hip arthroplasty (1977) J. Bone Joint Surg., 59 A, pp. 862-865; Verne, J., Sannie, C., Etude de l'action toxique des cations sur les fibroblastes cultivés in vitro (1933) Compt. Rend. Acad. Sci., 196, pp. 1246-1247; Kirkpatrick, C.J., A critical view of current and proposed methodologies for biocompatibility testing: Cytotoxicity in vitro (1992) Regul. Affairs, 4, pp. 13-22; Pereira, M.L., Silva, A., Tracana, R., Carvalho, G.S., Toxic effects caused by stainless steel corrosion products on mouse seminiferous cells (1994) Cytobios, 77, pp. 73-80; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Chromium accumulation and ultrastructural changes in the mouse liver caused by stainless steel corrosion products (1995) J. Mater. Sci. Mater. Med., 6, pp. 523-527; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Stainless steel corrosion products cause alterations on mouse spleen cellular populations (1995) J. Mater. Sci. Mater. Med., 6, pp. 56-61; Bravo, I., Sousa, S.R., Carvalho, G.S., Barbosa, M., Metals electrochemically dissolved in human serum inhibit T-lymphocyte function (1992) Advances in Biomaterials, pp. 7-11. , P. J. Doherty et al. (eds.), Amsterdam, Elsevier; Carvalho, G.S., Castanheira, M., Diogo, I., Abreu, A.M., Sousa, J.P., Loon, J.A., Blitterswijk, C.A., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1995) J. Mater. Sci. Mater. Med., 7, pp. 77-83; Evans, E.M., Freeman, M.A.R., Miller, A.J., Vernon-Roberts, B., Metal sensitivity as a cause of bone necrosis and loosening of the prosthesis in total joint replacement (1974) J. Bone Joint Surg., 56 B, pp. 626-642; Betts, F., Wright, T., Salvati, E.A., Boskey, A., Mansal, M., Cobalt alloy metal debris in periarticular tissues from total hip revision arthoplasties (1992) Clin. Orthop., 278, pp. 75-82; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralization by osteoblast-like cells: Part 1-Retardation of tissue mineralization by metal salts (1998) Biomaterials, 19, pp. 13-21; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionized calcium in osteoblast-like cell culture medium (1996) Electroanalysis, 8, pp. 1174-1178; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9, pp. 791-795; Morais, S., Carvalho, G.S., Sousa, J.P., Electrochemical characterization of iron species in osteoblast-like cell culture medium (1995) Port. Electrochim. Acta, 13, pp. 483-487; Morais, S., Carvalho, G.S., Sousa, J.P., Determination of nickel in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with mercury microelectrodes (1997) Electroanalysis, 9, pp. 422-426; Morais, S., Carvalho, G.S., Sousa, J.P., Optimization study for nickel quantification in cell culture medium using mercury film microelectrodes (1996) Port. Electrochim. Acta, 14, pp. 267-272; Morais, S., Carvalho, G.S., Sousa, J.P., Chromium determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode J. Trace Elements Med. Biol., , in press; Nurnberg, H.W., The voltammetric approach in trace metal chemistry of natural waters and atmospheric precipitation (1984) Anal.Chim. Acta, 164, pp. 1-21; Merritt, K., Wortman, R.S., Millard, M., Brown, S.A., XPS analysis of 316 LVM corroded in serum and in saline (1983) Biomater. Med. Devices Artif. Org., 11, pp. 115-127; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res., 254, pp. 317-330; Fiske, H., Subbarow, Y., The colorimetric determination of phosphorus (1925) J. Biol. Chem., 66, pp. 373-400; Vrouwenvelder, W.C.A., Groot, C.G., De Groot, K., Histological and biochemical evaluation of osteoblasts cultured on bioactive glass, hydroxylapatite, titanium alloy, and stainless steel (1993) J. Biomed. Mater. Res., 27, pp. 465-475; Bessey, O.A., Lowry, O.H., Breck, M.J., A method for the rapid determination of alkaline phosphatase with five cubic millimeters of serum (1946) J. Biol. Chem., 164, pp. 321-326; Karster, U., Wollenberger, A., Improvements in the ethidium bromide method for direct fluorometric estimation of DNA and RNA in cell and tissue homogenates (1977) Anal. Biochem., 77, pp. 464-470; McGee-Russell, S.M., Histochemical methods for calcium (1958) J. Histochem. Cytochem., 6, pp. 22-42; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulte formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Tassinari, M.S., Stein, G.S., Lian, J.B., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J. Cell Physiol., 143, pp. 213-221; Gotoh, Y., Hiraiwa, K., Narajama, M., In vitro mineralization of osteoblastic cells derived from human bone (1990) Bone Miner., 8, pp. 239-250; Cheng, S.L., Yang, J.W., Rifas, L., Zhang, S.F., Avioli, L.V., Differentiation of human bone marrow osteogenic stromal cells in vitro. Induction of the osteoblast phenotype by dexamethasone (1994) Endocrinology, 134, pp. 277-286; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Berridge, V., Tan, A.S., Characterization of the cellular reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT): Subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch. Biochem. Biophys, 303, pp. 474-482; Ciapetti, G., Cenni, E., Stea, S., Pizzoferrato, A., In vitro evaluation of cell/biomaterial interaction by MTT assay (1993) Biomaterials, 14, pp. 359-364; Sgouras, D., Duncan, R., Methods for the evaluation of biocompatibility of soluble synthetic polymers which have potential for biomedical use: 1-Use of the tetrazolium-based colorimetric assay (MTT) as a preliminary screen for evaluation of in vitro cytotoxicity (1990) J. Mater. Sci. Mater. Med., 1, pp. 61-68; Martin, A., Clynes, M., Comparison of 5 microplate colorimetric assays for in vitro cytotoxicity testing and cell proliferation assays (1993) Cytotechnology, 11, pp. 49-58; Stein, G.S., Lion, J.B., Molecular mechanisms mediated proliferation-differentiation interrelationships during progressive development of the osteoblast phenotype: Update 1995 (1995) Endosc. Rev., 4, pp. 290-297; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., The ultradtructure of the bone hydroxyapatite interface in vitro (1992) J. Biomed, Mater. Res., 26, pp. 1365-1382; Davies, J.E., Chernecky, R., Lowenberg, B., Shiga, A., Deposition and resorption of calcified matrix in vitro by rat marrow cells (1991) Cells Mater., 1, pp. 3-15; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., De Bruijn, J.D., Van Blitterswijk, C.A., Effects of AISI 316L corrosion products in in vitro bone formation (1998) Biomaterials, 19, pp. 999-1007; Pohler, E.M., Degradation of metallic orthopedic implants (1983) Biomaterials in Reconstructive Surgery, pp. 158-228. , L. R. Rubin (ed.), C. V. Mosby, St. Louis, Missouri; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Miner., 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone Miner., 17, pp. 15-29; Chung, C.H., Golub, E.E., Forbes, E., Tokuoka, T., Shapiro, I.M., Mechanisms of action of β-glycerophosphate on bone cell mineralization (1992) Calcif. Tissue Int., 51, pp. 305-311; Boskey, A.L., Stiner, D., Doty, S.B., Binderman, I., Levoy, P., Studies of mineralization in tissue culture: Optimal conditions for cartilage calcification (1992) Bone Miner., 16, pp. 11-36; Rae, T., The toxicity of metals used in orthopaedic prostheses (1981) J. Bone Joint Surg., 63 B, pp. 435-440; Webb, M., Weinzierl, S.M., Uptake of 63Ni 2+ from its complexes with proteins and other ligands by mouse dermal fibroblasts in vitro (1972) Br. J. Cancer, 26, pp. 292-298; Katz, S.A., Salem, H., The toxicology of chromium with respect to its speciation: A review (1993) J. Appl.Toxicol., 13, pp. 217-224; Pules, D.A., Huh, W.W., Acute toxicity of metal ions in cultures of osteogenic cells derived from bone marrow stromal cells (1995) J. Appl. Biomater., 6, pp. 109-116; Thompson, G.J., Pules, D.A., Effects of sublethal metal ion concentrations on osteogenic cells derived from bone marrow stromal cells (1995) J. Appl. Biomater., 6, pp. 249-258
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; alkaline phosphatase; animal cell; Animal cell culture; Animals; article; Biocompatible Materials; Biodegradation; biomineralization; Bioprosthesis; Bone; Bone and Bones; bone atrophy; bone marrow; Calcification, Physiologic; Calcium; calcium ion; Catalyst activity; Cells, Cultured; Chromium; controlled study; Corrosion; Corrosion products; Enzymes; Implants (surgical); metal implantation; mineralization; Nickel; nonhuman; osteoblast; Osteoblast-like cells; phosphate; phosphorus; prosthesis loosening; rat; Rats; Scanning electron microscopy; Stainless steel; Stainless steel corrosion products; Steel; Steel corrosion; tissue necrosis; transmission electron microscopy

Effects of AISI 316L corrosion products in in vitro bone formation - Morais, S.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S.; De Bruijn, J.D.; Van Blitterswijk, C.A. (BiomaterialsBiomaterials, 1998)
Rat bone marrow cells were cultured in experimental conditions that favour the proliferation and differentiation of osteoblastic cells (i.e., 2.52 x 10
Cited By (since 1996): 38Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(97)00234-2PubMed ID: 9692798Language of Original Document: EnglishCorrespondence Address: Morais, S.; Universidade do Porto, Porto, PortugalChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Calcium Phosphates; Calcium, 7440-70-2; Phosphorus, 7723-14-0; Stainless Steel, 12597-68-1References: Spector, M., Cease, C., Tong-Li, X., The local tissue response to biomaterials (1989) Crit Rev Biocompat, 5, pp. 269-295;Van Blitterswijk, C.A., Bakker, D., Hesseling, S.C., Koerten, H.K., Reactions of cells at implant surfaces (1991) Biomaterials, 12, pp. 187-193; Bagambisa, F.B., Kappert, H.F., Schilli, W., Interfacial reactions of osteoblasts to dental and implant materials (1994) J Oral Maxillofac Surg, 52, pp. 52-56; Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., Initial bone matrix formation at the hydroxyapatite interface in vivo (1995) J Biomed Mat Res, 29, pp. 89-99; Pilliar, R.M., Porous-surface metallic implants for orthopedic applications (1987) J Biomed Mat Res, 21 (A1), pp. 1-33; Bobyn, J.D., Tanzer, M., Drygier, J.J., Du Joune, A.R., Brooks, C.E., Concerns with modularity in total hip arthroplasty (1994) Clin Orthop, 298, pp. 27-36; Bartolozzi, A., Black, J., Chromium concentrations in serum, blood clot and urine from patients following total hip arthroplasty (1985) Biomaterials, 6, pp. 2-8; Dorr, L.D., Blocbaum, R., Emmanual, J., Meldrum, R., Histologic, biochemical and ion analysis of tissue and fluids retrieved during total hip arthroplasty (1990) Clin Orthop, 261, pp. 82-95; Hennig, F.F., Raithel, H.J., Schaller, K.H., Dohler, J.R., Nickel-chromand cobalt-concentrations in human tissue and body fluids of hip prosthesis patients (1992) J Trace Elem Electrolytes Health Dis, 6, pp. 239-243; Evans, E.M., Freeman, M.A.R., Miller, A.J., Vernon-Roberts, B., Metal sensitivity as a cause of bone necrosis and loosening of the prosthesis in total joint replacement (1974) J Bone Jt Surg, 56 B, pp. 626-642; Deutman, R., Rulder, T.J., Brian, R., Nater, J.P., Metal sensitivity before and after total hip arthroplasty (1977) J Bone Jt Surg, 59 A, pp. 862-865; Huo, M.H., Salvati, E.A., Lieberman, Jr., Betts, F., Bansal, M., Metallic debris in femoral endoseolysis in failed cemented total hip arthroplasties (1992) Clin Orthop, 276, pp. 157-168; Kirkpatrick, C.J., Mittermayer, C., Theoretical and practical aspects of testing potential biomaterials in vitro (1990) J Mat Mat Med, 1, pp. 9-13; Kirkpatrick, C.J., A critical view of current and proposed methodologies for biocompatibility testing: Cytotoxicity in vitro (1992) Regulatory Affairs, 4, pp. 13-22; Pizzoferrato, A., Ciapetti, G., Stea, S., Cell culture methods for testing biocompatibility (1994) Clin Mat, 15, pp. 173-190; Bizios, R., Mini review: Osteoblasts: An in vitro model of bone-implant interactions (1994) Biotechnol and Bioeng, 43, pp. 582-585; Pules, D.A., Huh, W.W., Acute toxicity of metal ions in cultures of osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 109-116; Thompson, G.J., Pules, D.A., Effects of sublethal metal ion concentrations on osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 249-258; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., Effects of Co-Cr corrosion products and corresponding separate metal ions on human osteoblast-like cell cultures (1996) J Mater Sc Mater Med, 7, pp. 291-296; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., The use of rat, rabbit or human bone marrow derived cells for cytocompatibility evaluation of metallic elements (1997) J Mater Sc Mater Med, 8, pp. 233-238; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralisation by osteoblast-like cells: Part 1 - Retardation of tissue mineralisation by metal salts Biomaterials 1998; Pereira, M.L., Silva, A., Tracana, R., Carvalho, G.S., Toxic effects caused by stainless steel corrosion products on mouse seminiferous cells (1994) Cytobios, 77, pp. 73-80; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Chromium accumulation and ultrastructural changes in the mouse liver caused by stainless steel corrosion products (1995) J Mater Sci Mater Med, 6, pp. 523-527; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Stainless steel corrosion products cause alterations on mouse spleen cellular populations (1995) J Mater Sci Mater Med, 6, pp. 56-61; Bravo, I., Sousa, S.R., Carvalho, G.S., Barbosa, M., Metals electrochemically dissolved in human serum inhibit T-lymphocyte function (1992) Advances in Biomaterials, pp. 7-11. , Doherty PJ et al., editors. Amsterdam: Elsevier; Carvalho, G.S., Castanheira, M., Diogo, I., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1995) J Mater Sci Mater Med, 7, pp. 77-83; Pohler, O.E.M., Degradation of metallic orthopedic implants Biomaterials in Reconstructive Surgery, pp. 158-228. , Rubin LR, editor. St. Louis: C. V. Mosby, 1983; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tiss Res, 254, pp. 317-330; McGee-Russell, S.M., Histochemical methods for calcium (1958) J Histochem Cytochem, 6, pp. 22-42; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionized calcium in osteoblast-like cell culture medium (1996) Electroanalysis, 8, pp. 1174-1178; Fiske, C.H., Subbarow, Y., The colorimetric determination of phosphorus (1925) J Biol Chem, 66, pp. 373-400; Miller, J.C., Miller, J.N., (1993) Statistics for Analytical Chemistry (3rd Ed.), pp. 32-35. , Massen M, Tyson J, Stockwell P, Miller J, Chalmers R, Harwood E, editors. New York, London: Ellis Horwood, PTR Prentice Hall; De Bruijn, J.D., Cpat, K., De Groot, K., Van Blitterswijk, C.A., The ultrastructure of the one-hydroxyapatite interface in vitro (1992) J Biomed Mat Res, 26, pp. 1365-1382; Davies, J.E., Chernecky, R., Lowenberg, B., Shiga, A., Deposition and resorption of calcified matrix in vitro by rat marrow cells (1991) Cells and Mat, 1, pp. 3-15; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulte formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 143, pp. 213-221; Gotoh, Y., Hiraiwa, K., Narajama, M., In vitro mineralization of osteoblastic cells derived from human bone (1990) Bone Min, 8, pp. 239-250; Cheng, S.L., Yang, J.W., Riffins, L., Differentiation of human bone marrow osteogenic stromal cells in vitro. Induction of the osteoblast phenotype by dexamethasone (1994) Endocrinology, 134, pp. 277-286; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone Min, 17, pp. 15-29; Boskey, A.L., Stiner, D., Doty, S.B., Binderman, I., Levoy, P., Studies of mineralization in tissue culture: Optimal conditions for cartilage calcification (1992) Bone Min, 16, pp. 11-36; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Min, 14, pp. 27-40; Chung, C.H., Golub, E.E., Forbes, E., Mechanisms of action of β-glycerophosphate on bone cell mineralization (1992) Calcif Tissue Int, 51, pp. 305-311
Keywords: Absorption spectroscopy; alkaline phosphatase; animal cell; Animal cell culture; Animals; article; ascorbic acid; atomic absorption spectrometry; Bioassay; Biomaterials; bone development; bone marrow cell; Bone Marrow Cells; Calcium; Calcium phosphates; Cell culture; Cell Death; Cells, Cultured; Corrosion; Corrosion products; culture medium; dexamethasone; electrochemical analysis; electrochemistry; Enzymes; glycerophosphate; histochemistry; Histocytochemistry; in vitro study; male; metal ion; Mineralisation; mineralization; nonhuman; ossification; osteoblast; Osteoblast-like cells; Osteoblasts; phosphate; Phosphate minerals; phosphorus; priority journal; rat; Rats; Rats, Wistar; Scanning electron microscopy; Slurries; Stainless steel; Stainless steel 316L; Stainless-steel corrosion products; Steel corrosion

Evaluation of nickel toxicity on liver, spleen, and kidney of mice after administration of high-dose metal ion - Pereira, M.C.; Pereira, M.L.; Sousa, J.P. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1998)
The toxic effects caused by nickel (Ni) per si were explored by performing in vivo studies on mice following subcutaneous administration of a metallic solution of nickel at 1, 2, 3, and 4 weeks to evaluate the side effects of this metal ion when released from stainless steel implants. Other groups were similarly injected with HBSS and used as controls. Accumulation of Ni ions on liver, spleen, and kidney was assessed by an electrochemical method, adsorptive stripping voltammetry (AdSV) using microelectrodes, and atomic absorption spectrometry (AAS). Alterations of those organs induced by Ni ions were studied, showing that several histological changes had been induced. Chemical analysis and histological features indicate that Ni is partially accumulated in the study organs.The toxic effects caused by nickel (Ni) per si were explored by performing in vivo studies on mice following subcutaneous administration of a metallic solution of nickel at 1, 2, 3, and 4 weeks to evaluate the side effects of this metal ion when released from stainless steel implants. Other groups were similarly injected with HBSS and used as controls. Accumulation of Ni ions on liver, spleen, and kidney was assessed by an electrochemical method, adsorptive stripping voltammetry (AdSV) using microelectrodes, and atomic absorption spectrometry (AAS). Alterations of those organs induced by Ni ions were studied, showing that several histological changes had been induced. Chemical analysis and histological features indicate that Ni is partially accumulated in the study organs.
Cited By (since 1996): 27Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(199804)40:1<40::AID-JBM5>3.0.CO;2-RPubMed ID: 9511097Language of Original Document: EnglishCorrespondence Address: Sousa, J.P.; Instituto de Engenharia Biomedica, Faculdade de Engenharia, Universidade do Porto, Praca Coronel Pacheco, 1, 4050 Porto, PortugalChemicals/CAS: Nickel, 7440-02-0References: Cigada, A., Rondelli, G., Vicentini, B., Brunella, F., Dallaspezia, G., Corrosion behavior of high nitrogen stainless steels for biomedical applications (1994) Compatibility of Biomedical Implants, pp. 185-195. , P. Kovacs and N. S. Istephanous (eds.), The Electrochemical Society, Inc., Pennington, New Jersey;Bumgardner, J.D., Lucas, L.C., An evaluation of the corrosion properties and cellular compatibility of nickel-based dental casting alloys (1994) Compatibility of Biomedical Implants, pp. 241-252. , P. Kovacs and N. S. Istephanous (eds.), The Electrochemical Society, Inc., Pennington, New Jersey; Williams, D.F., (1990) Encyclopedia of Medical and Dental Materials, , Pergamon Press, Oxford; Muller, A.W.J., Maessen, F.J.M.J., Davidson, C.L., Determination of the corrosion rates of six dental NiCrMo alloys in an artificial saliva by chemical analysis of the medium using ICP-AES (1990) Dent. Mater., 6, pp. 63-68; Bumgardner, J.D., Lucas, L.C., Surface analysis of nickel-chromium dental alloys (1993) Dent. Mater., 9, pp. 252-259; Williams, D.F., (1981) Systemic Aspects of Biocompatibility, 1-2. , CRC Press, Boca Raton, Florida; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Stainless steel products cause alterations on mouse spleen cellular populations (1995) J. Mater. Sci. Mater. Med., 6, pp. 56-61; Tracana, R.B., Sousa, J.P., Carvalho, G.S., Mouse inflammatory response to stainless steel corrosion products (1994) J. Mater. Sci. Mater. Med., 5, pp. 596-600; Jacks, J.J., Skiper, A.K., Black, J., Urban, R.M., Galante, J.O., Release and excretion of metal in patients who have a total hip replacement component made of titanium base alloy (1991) J. Bone Joint Surg., 73 A, pp. 1475-1486; Stulberg, B.N., Merrit, K., Bawer, T.W., Metallic wear debris in metal backed patellar failure (1994) J. Appl. Biomater., 5, pp. 9-16; Panigutti, M.A., Merrit, K., Bruner, R.J., Kraay, M.J., Brown, S.A., Correlation of allergy, metal levels, implant alloy, and implant damage in patients undergoing revision joint arthroplastics (1992) Trans. Soc. Biomater., 15, p. 7; Abreu, A.M., Tracana, R.B., Carvalho, G.S., Sousa, J.P., Determination of metal ions released from metallic biomaterials using absorption spectroscopy and microelectrodes (1995) Biomed. Lett., 52, pp. 133-148; (1986) Health Assessment Document for Nickel and Nickel Compounds, , EPA/600/8-83/012FF, U.S. Environmental Protection Agency, Research Triangle Park, North Carolina; Black, J., (1988) Orthopedic Biomaterials in Research and Practice, , Churchill Livingstone, New York; Nieboer, E., Rossetto, F.E., Menon, C.R., Toxicology of nickel compounds (1980) Nickel Toxicology, pp. 359-401. , S. S. Brown and F. W. Sunderman, Jr. (eds.), Academic Press, Inc., New York; Pereira, M.L., Pereira, M.C., Sousa, J.P., Evaluation of nickel effects on mouse liver: Tissue response and metal ion accumulation (1995) Biomed. Lett., 52, pp. 235-244; Pereira, M.C., Faria, J.L., Reis, M.L., Sousa, J.P., Nickel quantification in mice organs by adsorptive stripping voltammetry using mercury microelectrodes (1996) Electroanalysis, 9, pp. 1-5; Black, J., Systemic distribution and excretion (1981) Biomedical Engineering and Instrumentation, p. 180. , R. Plonsey and J. L. Katz (eds.), Marcel Dekker, Inc., New York; Pohler, O.E.M., Degradation of metallic orthopedic implants (1983) Biomaterials in Reconstructive Surgery, p. 197. , L. R. Rugin (ed.), The C. V. Mosby Company, St. Louis; Ross, M.H., Romrell, L.J., (1989) Histology - A Text and Atlas, , Williams and Wilkins, New York
Keywords: Absorption spectroscopy; Adsorptive stripping voltammetry; animal experiment; animal tissue; Animals; article; atomic absorption spectrometry; biomaterial; body weight; controlled study; Dose-Response Relationship, Drug; electrochemistry; Evaluation Studies; histology; Implants (surgical); Kidney; Liver; liver toxicity; Living systems studies; Mice; Microelectrodes; mouse; nephrotoxicity; Nickel; nonhuman; potentiometry; Spectrophotometry, Atomic; Spleen; spleen injury; Stainless steel; toxicity

Flow cytometry for assessing biocompatibility - Lopes, M.A.; Knowles, J.C.; Kuru, L.; Santos, J.D.; Monteiro, F.J.; Olsen, I. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1998)
Flow cytometry (FCM) was examined as a possible procedure for measuring in vitro the biocompatibility of implant materials for orthopedic and dental surgery. The human osteoblast-like cell line MG63 was grown on hydroxyapatite (HA) and P 2O 5 glass-reinforced HA composite discs and compared with the same cells grown on polystyrene culture dishes. While morphological observation at the light and electron microscopic levels showed no major deleterious effects, FCM indicated that cell size was somewhat reduced, particularly by growth on the HA composite. Moreover, this material also appeared to delay the progression of the cells from the G0/G1 into the S phase of the cell cycle. In addition to this low level of inhibition of cell growth relative to control cultures, FCM analysis also demonstrated that the glass-reinforced HA caused some down-regulation of the expression of osteocalcin and fibronectin, two antigens which play a vital part in the integrity and function of bone and soft connective tissue, respectively. These results thus show, first, that although HA and the HA composite used in these experiments were generally biocompatible, they nevertheless had certain suboptimal effects on the cells; and second, that FCM could be a highly useful procedure for effectively screening and evaluating important biological responses to implant materials. Flow cytometry (FCM) was examined as a possible procedure for measuring in vitro the biocompatibility of implant materials for orthopedic and dental surgery. The human osteoblast-like cell line MG63 was grown on hydroxyapatite (HA) and P 2O 5 glass-reinforced HA composite discs and compared with the same cells grown on polystyrene culture dishes. While morphological observation at the light and electron microscopic levels showed no major deleterious effects, FCM indicated that cell size was somewhat reduced, particularly by growth on the HA composite. Moreover, this material also appeared to delay the progression of the cells from the G0/G1 into the S phase of the cell cycle. In addition to this low level of inhibition of cell growth relative to control cultures, FCM analysis also demonstrated that the glass-reinforced HA caused some down-regulation of the expression of osteocalcin and fibronectin, two antigens which play a vital part in the integrity and function of bone and soft connective tissue, respectively. These results thus show, first, that although HA and the HA composite used in these experiments were generally biocompatible, they nevertheless had certain suboptimal effects on the cells; and second, that FCM could be a highly useful procedure for effectively screening and evaluating important biological responses to implant materials.
Cited By (since 1996): 33Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(19980915)41:4<649::AID-JBM17>3.0.CO;2-9PubMed ID: 9697038Language of Original Document: EnglishCorrespondence Address: Olsen, I.; Department of Periodontology, Eastman Dental Institute, University of London, 256 Gray's Inn Rd., London WC1X 8LD, United KingdomChemicals/CAS: Biocompatible Materials; Collagen, 9007-34-5; Dental Implants; Fibronectins; Osteocalcin, 104982-03-8References: Kirkpatrick, C.J., A critical view of current and proposed methodologies for biocompatibility testing: Cytotoxicity in vitro (1992) Regul. Affairs, 4, pp. 13-32;Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Ariola, C.R., Granchi, D., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin. Mater., 15, pp. 173-190; Puleo, D.A., Preston, K.E., Shaffer, J.B., Bizios, R., Examination of osteoblast-orthopaedic biomaterial interactions using molecular techniques (1993) Biomaterials, 14, pp. 111-114; Clifford, C.J., Downes, S., A comparative study of the use of colorimetric assays in the assessment of biocompatibility (1996) J. Mater. Sci. Mater. Med., 7, pp. 637-643; Macey, M.G., (1994) Flow Cytometry: Clinical Applications, , Blackwell Scientific Publications, Oxford; Salzman, G.C., Singham, S.B., Johnston, R.G., Bohren, C.F., Light scattering and cytometry (1990) Flow Cytometry and Sorting, pp. 81-107. , M. R. Melamed, T. Lindmo, and M. L. Mendelsohn (eds.), Wiley-Liss, New York; Corver, W.E., Cornelisse, C.J., Fleuren, G.J., Simultaneous measurement of two cellular antigens and DNA using fluorescein-isothiocyanate, R-phycoerythrin and propidium iodide on a standard FACScan (1994) Cytometry, 15, pp. 117-128; Macon, W.R., Salhany, K.E., TI- T-cell subset analysis of paraffin-embedded peripheral T-cell lymphomas (PTCLs) with correlation of CD4/CD8 results by flow cytometry (FACs) (1997) Lab. Invest., 76, p. 753; Kuru, L., Parkar, M.H., Griffiths, G.S., Newman, H.N., Olsen, I., Flow cytometry analysis of functionally distinct gingival and periodontal ligament cells (1998) J. Dent. Res., 77, pp. 555-564; Kamiya, I., Okuda, K., Hara, K., Flow cytometric identification and detection of Porphromonas gingivalis by an LPS specific monoclonal antibody (1994) J. Periodontol., 65, pp. 309-315; Sumner, H., Abraham, D., Bou-Gharios, G., Plater-Zyberk, C., Olsen, I., Simultaneous measurement of cell surface and intracellular antigens by multiple flow cytometry (1991) J. Immunol. Methods, 136, pp. 259-267; Beauchamp, J.R., Abraham, D.J., Bou-Gharios, G., Partridge, T.A., Olsen, I., Expression and function of adhesion molecules during differentiation of human skeletal muscle in culture (1992) Am. J. Pathol., 140, pp. 387-401; Abraham, D., Lupoli, S., McWhirter, A., Plater-Zyberk, C., Piela, T.H., Korn, J., Olsen, I., Black, C., Expression and function of surface antigens on scleroderma fibroblasts (1991) Arthritis Rheum., 34, pp. 1164-1172; Bou-Gharios, G., Osman, J., Black, C., Olsen, I., Excess matrix accumulation in scleroderma is caused partly by differential regulation of stromelysin and TIMP-1 synthesis (1994) Clin. Chim. Acta, 231, pp. 69-78; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Best, S., Sim, B., Kayser, M., Downes, S., The dependence of osteoblastic response on variations in the chemical composition and physical properties of hydroxyapatite (1997) J. Mater. Sci. Mater. Med., 8, pp. 97-103; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Dean, D.D., Boyan, B.D., Effect of titanium surface roughness on proliferation, differentiation and protein synthesis of human osteoblast-like cells (MG-63) (1995) J. Biomed. Mater. Res., 29, pp. 389-401; Granchi, D., Stea, S., Ciapetti, G., Savarino, L., Cavedagna, D., Pizzoferatto, A., In vitro effects of bone cements on the cell cycle of osteoblast-like cells (1995) Biomaterials, 16, pp. 1187-1192; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Scharla, S.H., Strong, D.D., Rosen, C., Mohan, S., Holick, M., Baylink, D.J., Linkhart, T.A., 1,25-Dihydroxyvitamin D3 increases secretion of insulin-like growth factor binding protein-4 (IGFBP-4) by human osteoblast-like cells in vitro and elevates IGFBP-4 serum levels in vivo (1993) J. Clin. Endocrinol. Metabol., 77, pp. 1190-1197; De Bart, A.C., Quax, P.H., Lowik, C.W., Verheijen, J.H., Regulation of plasminogen activation, matrix metalloproteinases and urokinase-type plasminogen activator-mediated extracellular matrix degradation in human osteosarcoma cell line MG63 by interleukin-1 alpha (1995) J. Bone Min. Res., 19, pp. 1374-1384; Barille, S., Collette, M., Bataille, R., Amiot, M., Myeloma cells upregulate interleukin-6 secretion in osteoblastic cells through cell-to-cell contact but downregulate osteocalcin (1995) Blood, 86, pp. 3151-3159; Maillard, C., Malaval, L., Delmas, P.D., Immunological screening of SPARC/osteonectin in nonmineralized tissue (1992) Bone, 13, pp. 257-264; Bou-Gharios, G., Osman, J., Atherton, A., Monoghan, P., Vancheeswaran, R., Black, C., Olsen, I., Expression of ectopeptidases in scleroderma (1995) Ann. Rheum. Dis., 54, pp. 111-116; Goseki, T., Shimizu, N., Iwasawa, T., Takiguchi, H., Abiko, Y., Effects of in vitro cellular aging on alkaline phosphatase, cathepsin activities and collagen secretion of human peridontal ligament-derived cells (1996) Mech. Age. Dev., 91, pp. 1761-11183; Hallab, N.J., Bundy, K.J., O'Connor, K., Clark, R., Moses, R.L., Cell adhesion to biomaterials: Correlations between surface charge, surface roughness, adsorbed protein and cell morphology (1995) J. Long-Term Effects Med. Implants, 5, pp. 209-231; Kieswetter, K., Schwartz, Z., Hummert, T.W., Cochran, D.L., Simpson, J., Sean, D.P., Boyan, B.D., Surface roughness modulates the local production of growth factors and cytokines by osteoblast-like MG-63 cells (1996) J. Biomed. Mater. Res., 32, pp. 55-63; Altankov, G., Grinnell, F., Groth, T., Studies on the biocompatibility of materials: Fibroblast reorganization of substratumbound fibronectin on surfaces varying in wettability (1996) J, Biomed. Mater. Res., 30, pp. 385-391; Chesmel, K.D., Clark, C.C., Brighton, C.T., Black, J., Cellular response to chemical and morphologic aspects of biomaterial surfaces. II. The biosynthetic and migratory response of bone cell populations (1995) J. Biomed. Mater. Res., 29, pp. 1101-1110; Nishizawa, K., Toriyama, M., Suzuki, T., Kawamoto, Y., Yokogawa, Y., Nagae, H., Effects of the surface wettability and zeta potential of bioceramics on the adhesiveness of anchorage-dependent animal cells (1993) J. Ferment. Bioeng., 75, pp. 435-437; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J. Biomed. Mater. Res., 39, pp. 244-251
Keywords: antigen expression; Antigens; Biocompatibility; Biocompatible Materials; biomaterial; Biomaterials; Biomedical engineering; Bone and Bones; bone prosthesis; Cell culture; cell cycle; cell cycle s phase; Cell Line; Cell size; cell ultrastructure; Cells; Collagen; conference paper; Dental Implants; dentistry; extracellular matrix; Fibronectin; Fibronectins; flow cytometry; Glass fiber reinforced plastics; growth inhibition; human; human cell; Humans; hydroxyapatite; Implants; Implants (surgical); Microscopy, Electron, Scanning; mitosis inhibition; morphology; orthopedics; Osteoblasts; osteocalcin; Polystyrenes; Prostheses and Implants; prosthesis material; Tissue; tooth prosthesis

In situ characterization of the p-Si/NH 4F interface during dissolution in the current oscillations regime - Cattarin, S.; Chazalviel, J.-N.; Da Fonseca, C.; Ozanam, F.; Peter, L.M.; Schlichthörl, G.; Stumper, J. (Journal of the Electrochemical SocietyJ Electrochem Soc, 1998)
Several physicochemical properties of the p-Si/NH 4F interface have been monitored by in situ techniques in the regime of current oscillations. Comparison of evolution of infrared absorption, microwave reflectivity, electrode admittance, hydrogen evolution, and electron injection rate shows interesting correlations. An integrated description of the processes involved is attempted on the basis of the current models for the Si/acidic fluoride interface.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: JESOALanguage of Original Document: EnglishCorrespondence Address: Cattarin, S.; Ist. Polarografia ed E., C. N. R., 35100 Padova, ItalyReferences: Zhang, X.G., Collins, S.D., Smith, R.L., (1989) This Journal, 136, p. 1561;Smith, R.L., Collins, S.D., (1992) J. Appl. Phys., 71, pp. R1; Jung, K.H., Shih, S., Kwong, D.L., (1993) This Journal, 140, p. 3046; Lewerenz, H.J., Stumper, J., Pettenkofer, C., Greef, R., (1989) Electrochim. Acta, 34, p. 1729; Bitzer, T., Lewerenz, H.J., (1992) Surf. Sci., 269-270, p. 886; Lewerenz, H.J., Bitzer, T., Gruyters, M., Jacobi, K., (1993) This Journal, 140, pp. L44; Lewerenz, H.J., (1992) Electrochim. Acta, 37, p. 847; Chazalviel, J.-N., (1992) Electrochim. Acta, 37, p. 865; Ozanam, F., Chazalviel, J.-N., (1993) J. Electron Spec. Rel. Phenomena, 64-65, p. 395; Ozanam, F., Da Fonseca, C., Chazalviel, J.-N., (1995) Proc. Indian Acad. Sci. (Chem. Sci.), 107, p. 709; Da Fonseca, C., Ozanam, F., Chazalviel, J.-N., (1996) Surface Science, 365, p. 1; Stumper, J., Peter, L.M., (1991) J. Electroanal. Chem., 309, p. 325; Stumper, J., Greef, R., Peter, L.M., (1991) J. Electroanal. Chem., 310, p. 445; Blackwood, D.J., Borazio, A., Greef, R., Peter, L.M., Stumper, J., (1992) Electrochim. Acta, 37, p. 889; Gerischer, H., Lüke, M., (1988) Ber. Bunsenges. Phys. Chem., 92, p. 573; Chazalviel, J.-N., Ozanam, F., Etman, M., Paolucci, F., Peter, L.M., Stumper, J., (1992) J. Electroanal. Chem., 327, p. 343; Aggour, M., Giersig, M., Lewerenz, H.-J., (1995) J. Electroanal. Chem., 383, p. 67; Lehmann, V., (1996) This Journal, 143, p. 1313; Lewerenz, H.J., Aggour, M., (1993) J. Electroanal. Chem., 351, p. 159; Chazalviel, J.-N., Ozanam, F., (1992) This Journal, 139, p. 2501; Cattarin, S., Peter, L.M., Jason Riley, D., (1997) J. Phys. Chem. B, 101, p. 4071; Kirk, C.T., (1988) Phys. Rev. B, 38, p. 1255; Schlichtörl, G., Peter, L.M., (1994) This Journal, 141, pp. L171; Myamlin, V.A., Pleskov, Y.V., (1967) Electrochemistry of Semiconductors, p. 213. , Plenum Press, New York; Chazalviel, J.-N., Da Fonseca, C., Ozanam, F., To be publishedPankove, J.I., (1971) Optical Processes in Semiconductors, p. 75. , Prentice-Hall Inc., Englewood Cliffs, NJ; Tardella, A., Chazalviel, J.-N., (1985) Phys. Rev. B, 32, p. 2439; Peter, L.M., Schlichthörl, G., In preparationRappich, J., Timoshenko, V.Y., Dittrich, T., (1997) Ber. Bunsenges. Phys. Chem., 101, p. 139; Matsumura, M., Morrison, S.R., (1983) J. Electroanal. Chem., 147, p. 157; Franck, U.F., (1974) Faraday Symp. Chem. Soc., 9, p. 137
Keywords: Ammonium compounds; Ammonium fluoride; Dissolution; Electric currents; Electric Impedance; Electrochemical electrodes; Electron injection rate; Hydrogen; Interfaces (materials); Microwave reflectivity; Porous silicon

In vitro biomineralization by osteoblast-like cells I. Retardation of tissue mineralization by metal salts - Morais, S.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S. (BiomaterialsBiomaterials, 1998)
The cytocompatibility of stainless steel 316L (SS 316L) corrosion products was investigated with particular focus on the dose- and time-effect of electrochemically dissolved SS and the corresponding separate metal ions on osteogenic bone marrow derived cells. Type AISI 316L stainless steel (Fe 63.9%, Cr 18.0%, Ni 12.5%, Mo 2.8%, Si 1.2%, Mn 1.6% and C 0.025%, weight for weight) was anodically dissolved in Hank's Balanced Salt Solution (HBSS) and diluted to the following concentrations: 500 μgml
Cited By (since 1996): 39Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(97)00149-XPubMed ID: 9678845Language of Original Document: EnglishCorrespondence Address: Carvalho, G.S.; IEC, Universidade do Minho, Largo do Paco, 4719 Braga Codex, PortugalChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Calcium, 7440-70-2; Cations; Chromium, 7440-47-3; Iron, 7439-89-6; Metals; Nickel, 7440-02-0; Phosphates; Stainless Steel, 12597-68-1; Tetrazolium Salts; Thiazoles; thiazolyl blue, 298-93-1References: Evans, E.M., Freeman, M.A.R., Miller, A.J., Vernon-Roberts, B., Metal sensitivity as a cause of bone necrosis and loosening of the prosthesis in total joint replacement (1974) J Bone Jt Surg, 56 B, pp. 626-642;Deutman, R., Rulder, T.J., Brian, R., Nater, J.P., Metal sensitivity before and after total hip arthroplasty (1977) J Bone Jt Surg, 59 A, pp. 862-865; Bartolozzi, A., Black, J., Chromium concentrations in serum, blood clot and urine from patients following total hip arthroplasty (1985) Biomaterials, 6, pp. 2-8; Dorr, L.D., Blocbaum, R., Emmanual, J., Meldrum, R., Histologic, biochemical and ion analysis of tissue and fluids retrieved during total hip arthroplasty (1990) Clin Orthop, 261, pp. 82-95; Henning, F.F., Raithel, H.J., Schaller, K.H., Dohler, J.R., Nickel-, chromium- and cobalt-concentrations in human tissue and body fluids of hip prosthesis patients (1992) J Trace Elem Electrolytes Health Dis, 6, pp. 239-243; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., Effects of Co-Cr corrosion products and corresponding separate metal ions on human osteoblast-like cell cultures (1996) J Mater Sci Mater Med, 7, pp. 291-296; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., The use of rat, rabbit or human bone marrow derived cells for cytocompatibility evaluation of metallic elements (1997) J Mater Sci Mater Med, 8, pp. 233-238; Pules, D.A., Huh, W.W., Acute toxicity of metal ions in cultures of osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 109-116; Thompson, G.J., Pules, D.A., Effects of sublethal metal ion concentrations on osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 249-258; McGee-Russell, S.M., Histochemical methods for calcium (1958) J Histochem Cytochem, 6, pp. 22-42; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulate formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Wong, M., Rao, L.G., Li, H., Long-term effects of physiologic concentrations of dexamethasone on human bone derived cells (1990) J Bone Miner Res, 5, pp. 803-813; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 143, pp. 213-221; Gotoh, Y., Hiraiwa, K., Narajama, M., In vitro mineralisation of osteoblastic cells derived from human bone (1990) Bone Miner, 8, pp. 239-250; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralisation of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Miner, 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralisation of osteoid nodules in vitro (1992) Bone Miner, 17, pp. 15-29; Chung, C.H., Golub, E.E., Forbes, E., Mechanisms of action of β-glycerophosphate on bone cell mineralisation (1992) Calcif Tissue Int, 51, pp. 305-311; Schimdt, R., Kulbe, K.D., Long term cultivation of human osteoblasts (1993) Bone Miner, 20, pp. 211-221; Cheng, S.L., Yang, J.W., Riffins, L., Differentiation of human bone marrow osteogenic stromal cells in vitro. Induction of the osteoblast phenotype by dexamethasone (1994) Endocrinology, 134, pp. 277-286; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Fernandes, M.H., Costa, M.A., Carvalho, G.S., Mineralisation in serially passaged human alveolar bone cells (1997) J Mater Sci Mater Med, 8, pp. 73-76; Martin, A., Clynes, M., Comparison of 5 microplate colorimetric assays for in vitro cytotoxicity testing and cell proliferation assays (1993) Cytotechnology, 11, pp. 49-58; Sgouras, D., Duncan, R., Methods for the evaluation of biocompatibility of soluble synthetic polymers which have potential for biomedical use. 1. Use of the tetrazolium-based colorimetric assay (MTT) as a preliminary screen for evaluation of in vitro cytotoxicity (1990) J Mater Sci Mater Med, 1, pp. 61-68; Ciapetti, G., Cenni, E., Stea, S., Pizzoferrato, A., In vitro evaluation of cell/biomatrial interaction by MTT assay (1993) Biomaterials, 14, pp. 359-364; Yoshimura, T., Kurita, C., Hayata, M., Nagai, H., Diagnosis of drug allergy by the lymphocyte stimulation test with the MTT (3-(4,5-dimethyl thiazol-2-yl)-2,2-diphenyl tetrazolium bromide) assay (1993) Biol Pharm Bull, 16, pp. 686-689; Sasanaluckit, P., Albustany, K.R., Doherty, P.J., Williams, D.F., Biocompatibility of glass ionomer cements (1993) Biomaterials, 14, pp. 906-916; Carvalho, G.S., Castanheira, M., Diogo, I., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1996) J Mater Sci Mater Med, 7, pp. 77-83; Vrouwenvelder, W.C.A., Groot, C.G., De Groot, K., Histological and biochemical evaluation of osteoblasts cultured on bioactive glass, hydroxylapatite, titanium alloy and stainless steel (1993) J Biomed Mater Res, 27, pp. 465-475; Owen, M., Marrow stromal stem cells (1988) J Cell Sci, 10, pp. 63-76; Beresford, J.N., Osteogenic stem cells and the stromal system of bone and marrow (1989) Clin Orthop Rel Res, 240, pp. 270-280; Owen, T.A., Arohow, M., Shalhonb, V., Progressive development of the rat osteoblast phenotype in vitro: Reciprocal relationships in expression of genes associated with osteoblast proliferation during formation of bone extracellular matrix (1990) J Cell Phys, 143, pp. 420-430; Malaval, L., Modrowski, D., Gupta, K., Aubin, J.E., Cellular expression of bone related proteins during in vitro osteogenesis in rat bone marrow stromal cell cultures (1994) J Cell Phys, 158, pp. 555-572; Stein, G.S., Lion, J.B., Molecular mechanisms mediated proliferation-differentiation interrelationships during progressive development of the osteoblast phenotype: Update 1995 (1995) End Rev, 4, pp. 290-297
Keywords: Absorption spectroscopy; alkaline phosphatase; animal cell; Animalia; Animals; article; ascorbic acid; atomic absorption spectrometry; balanced salt solution; Bioassay; Biocompatibility; biomaterial; Biomaterials; biomineralization; bone marrow cell; bone mineralization; Bovinae; Calcification, Physiologic; Calcium; calcium phosphate; Carbon; Cations; Cattle; Cell Division; cell proliferation; cell survival; cell viability; Cells, Cultured; Chromium; controlled study; Corrosion; dexamethasone; electrochemistry; enzyme activity; Enzyme kinetics; glycerol 2 phosphate; histochemistry; Iron; Kinetics; manganese; metal ion; Metal ions; Metals; molybdenum; Nickel; nonhuman; Oryctolagus cuniculus; osteoblast; Osteoblast cells; Osteoblast-like cells; Osteoblasts; Phosphates; priority journal; rabbit; Rabbits; serum; Silicon; Stainless steel; Steel corrosion; Tetrazolium Salts; Thiazoles; Tissue culture

In vitro biomineralization by osteoblast-like cells II. Characterization of cellular culture supernatants - Morais, S.; Carvalho, G.S.; Faria, J.L.; Gomes, H.T.; Sousa, J.P. (BiomaterialsBiomaterials, 1998)
The quantification of total calcium, phosphorus, iron, chromium and nickel in cell culture medium by electrochemical or spectroscopic means may require digestion of samples. Nevertheless, when pH adjustment is performed for values higher than about 6.5, the formation of two phases occurs: a white precipitate and a clear solution. Analysing both phases using microelectrodes, atomic absorption spectrometry (AAS), diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy. X-ray dispersive (XRD) analysis, scanning electron microscopy (SEM) and energy dispersive spectroscopic (EDS) analysis, it was oberved that iron, chromium and nickel are not co-precipitating with the white solid phase. If quantification of calcium, phosphorus and magnesium is intended, a ten-fold dilution at least, must be performed to avoid most of these elements going into the precipitate. This knowledge is crucial if a mineralization study is going to be made.The quantification of total calcium, phosphorus, iron, chromium and nickel in cell culture medium by electrochemical or spectroscopic means may require digestion of samples. Nevertheless, when pH adjustment is performed for values higher than about 6.5, the formation of two phases occurs: a white precipitate and a clear solution. Analyzing both phases using microelectrodes, atomic absorption spectrometry (AAS), diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy, X-ray dispersive (XRD) analysis, scanning electron microscopy (SEM) and energy dispersive spectroscopic (EDS) analysis, it was observed that iron, chromium and nickel are not co-precipitating with the white solid phase. If quantification of calcium, phosphorus and magnesium is intended, a ten-fold dilution at least, must be performed to avoid most of these elements going into the precipitate. This knowledge is crucial if a mineralization study is going to be made.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(97)00150-6PubMed ID: 9678846Language of Original Document: EnglishCorrespondence Address: Carvalho, G.S.; IEC, Universidade do Minho, Largo do Paco, 4719 Braga Codex, PortugalChemicals/CAS: Calcium, 7440-70-2; Chromium, 7440-47-3; Culture Media; Iron, 7439-89-6; Metals; Nickel, 7440-02-0; Phosphorus, 7723-14-0; Stainless Steel, 12597-68-1References: Pereira, M.L., Silva, A., Tracana, R., Carvalho, G.S., Toxic effects caused by stainless steel corrosion products on mouse seminiferous cells (1994) Cytobios, 77, pp. 73-80;Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Chromium accumulation and ultrastructural changes in the mouse liver caused by stainless steel corrosion products (1995) J Mater Sci Mater Med, 6, pp. 523-527; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Stainless steel corrosion products cause alterations on mouse spleen cellular populations (1995) J Mater Sci Mater Med, 6, pp. 56-61; Bravo, I., Sousa, S.R., Carvalho, G.S., Barbosa, M., Metals electrochemically dissolved in human serum inhibit T-lymphocyte function (1992) Advances in Biomaterials, pp. 7-11. , Doherty PJ, et al., editors. Amsterdam: Elsevier; Carvalho, G.S., Castanheira, M., Diogo, I., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1995) J Mater Sci Mater Med, 7, pp. 77-83; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro bone formation in the presence of stainless steel corrosion products (1994) Poster Section, 11th European Conference on Biomaterials, , Pisa, Italy; Sousa, J.P., Requirements in materials for biosensors J Mater Sci Mater Med, , in press; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralisation by osteoblast like cells. I. Retardation of tissue mineralisation by metal salts (1998) Biomaterials, 19, pp. 13-21; Morais, S., Carvalho, G.S., Sousa, J.P., Determination of nickel in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with mercury microelectrodes (1997) Electroanalysis, 9 (5), pp. 422-426; Morais, S., Carvalho, G.S., Sousa, J.P., Optimization study for nickel quantification in cell culture medium using mercury film microelectrodes (1996) Portugaliae Electrochimica Acta, 14, pp. 267-272; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9, pp. 791-795; Morais, S., Carvalho, G.S., Sousa, J.P., Chromium determination in osteoblast-like cell culture medium by catalytic stripping voltammetry with a mercury microelectrode Electroanalysis, , submitted for publication; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionised calcium in osteoblast-like cell culture medium (1996) Electroanalysis, 8 (12), pp. 1174-1178; Morais, S., Carvalho, G.S., Sousa, J.P., Inorganic phosphorus determination in osteoblast-like cell culture for in vitro mineralisation study (1996) Poster Section, 15th Meeting of the Portuguese Chemical Society, , Porto; Pend, J., Jin, W., Anodic stripping voltammetric determination of trace lead in micro-samples with a mercury ultramicroelectrode (1992) Anal Chim Acta, 264, pp. 213-219; Pereira, M.C., Faria, J.L., Reis, M.L., Sousa, J.P., Nickel quantification in mice organs by adsorptive cathodic stripping voltammetry using mercury microelectrodes (1997) Electroanalysis, 9, p. 1501; Wurfels, W., Jackwerth, E., Stoeppler, M., Residues from biological materials after pressure decomposition with nitric acid. Part 3a (1989) Anal Chim Acta, 226, pp. 31-41; Wurfels, W., Jackwerth, E., Stoeppler, M., Residues from biological materials after pressure decomposition with nitric acid. Part 2a (1989) Anal Chim Acta, 226, pp. 17-30; Kotz, L., Henze, G., Kaiser, G., Pahlke, S., Veber, R., Tolg, G., Wet mineralisation of organic matrices in glassy carbon vessels in a pressure-bomb system for trace element analysis (1979) Talanta, 26, pp. 681-691; Nakamoto, K., (1970) Infrared Spectra of Inorganic and Coordination Compounds, 2nd Edn., , NY: Wiley Interscience; Lin-Vien, D., Colthup, N.B., Fateley, W.G., Grasselli, J.G., (1991) The Handbook of Infrared and Raman Characteristic Frequencies of Organic Molecules, , Boston: Academic Press; Walsh, W.R., Christiansen, D.L., Demineralized bone matrix as a template for mineral-organic composites (1995) Biomaterials, 16 (18), pp. 1363-1371; Koeneman, J., Lemons, J., Ducheyne, P., Lacefield, W., Magee, F., Calahan, K.J., Workshop on characterisation of calcium phosphate materials (1990) J Appl Biomater, 1, pp. 79-90; Mann, S., Webb, J., Williams, R.J.P., (1989) Biomineralization: Chemical and Biochemical Perspectives, , Germany: VCH, Weinheim; Evans, E.M., Freeman, M.A.R., Miller, A.J., Vernon-Roberts, B., Metal sensitivity as a cause of bone necrosis and loosening of the prosthesis in total joint replacement (1974) J Bone Jt Surg, 566, pp. 626-642; De Vernejoul, M.C., Pointillart, A., Golenzer, C.C., Metals in bone (1985) Lancaster, pp. 321-331. , Priest ND, editor. MTT; Kusec, R., Nikolic, V., Hancevic, J., Davila, S., Alkovic, V., Trace elements in periosteal callus and cortical bone after plating for fracture (1990) Periodicum Biologorum, 92 (3), pp. 325-327; Betts, F., Wright, T., Salvati, E.A., Boskey, A., Mansal, M., Cobalt alloy metal debris in periarticular tissues from total hip revision arthoplasties (1992) Clin Orthop, 278, pp. 75-82; Brien, W.W., Salvati, E.A., Betts, F., Metal levels in cemented total hip arthroplasty: A comparison of well-fixed and loose implants (1992) Clin Orthop, 276, pp. 66-74
Keywords: Absorption spectroscopy; Animals; article; atomic absorption spectrometry; Biomaterials; bone mineralization; Calcification, Physiologic; Calcium; Cell culture medium; Cells, Cultured; Chromium; Culture Media; culture medium; Diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy; electrochemistry; Energy dispersive spectroscopic analysis; Fourier transform infrared spectroscopy; Hydrogen-Ion Concentration; infrared spectroscopy; Iron; Magnesium; Metals; microelectrode; Microelectrodes; Nickel; nonhuman; osteoblast; Osteoblast cells; Osteoblasts; pH effects; phosphorus; precipitation; Precipitation (chemical); priority journal; Rabbits; Scanning electron microscopy; Spectrophotometry, Atomic; Spectroscopic techniques; Spectroscopy; Stainless steel; supernatant; Supernatants; Tissue culture; X ray analysis; X ray dispersive analysis

New starch-based thermoplastic hydrogels for use as bone cements or drug-delivery carriers - Pereira, C.S.; Cunha, A.M.; Reis, R.L.; Vázquez, B.; San Román, J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1998)
The development of new biodegradable hydrogels, based on corn starch/cellulose acetate blends, produced by free-radical polymerization with methyl methacrylate monomer (MMA) and/or an acrylic acid monomer (AA), is reported. The polymerization was initiated by a redox system consisting of a benzoyl peroxide and 4-dimethlyaminobenzyl alcohol at low temperature. These hydrogels may constitute an alternative to the materials currently used as bone cements or drug-delivery carriers. Swelling studies were carried out, as a function of pH and temperature, in buffered solutions. The xerogels were further characterized by Fourier transform-infrared spectroscopy. Tensile and compression tests, and dynamic mechanical thermal analysis were used to assess the mechanical performance of the developed materials. The fracture surfaces were observed by scanning electron microscopy. The developed materials are sensitive to the pH, showing a clear reversible transition in a relatively narrow interval of pH, which is just in the range of physiological conditions. These properties make the materials developed in this study very promising for biomedical applications. Fickian-type diffusion is the mechanism predominant in these systems, except for the composition with a higher concentration of AA, that corresponds to the most desirable kinetical behavior for controlled release (case II-transport mechanism). Furthermore, the results obtained in the mechanical tests are in the range of those reported for typical PMMA bone cements, showing that it is possible to develop partially degradable cements with an adequate mechanical behavior.
Cited By (since 1996): 67Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1008944127971Language of Original Document: EnglishCorrespondence Address: Reis, R.L.; INEB-Inst for Biomedical Engineering, Biomaterials Laboratory, Rua do Campo Alegre 823, 4150 Porto, Portugal; email: rgreis@fe.up.ptChemicals/CAS: acrylic acid, 10344-93-1, 79-10-7; alcohol, 64-17-5; benzoyl peroxide, 94-36-0; cellulose acetate, 9004-35-7; poly(methyl methacrylate), 39320-98-4, 9008-29-1; starch, 9005-25-8, 9005-84-9Tradenames: AA, Merck, Germany; BPO, Merck, Germany; Master-Bi Y101U, novamont, Italy; MMA, Merck, GermanyManufacturers: Merck, Germany; novamont, ItalyReferences: Peppas, N.A., Mikos, A.G., (1988) Hydrogels in Medicine and Pharmacy-Fundamentals, 1, p. 1. , edited by N. A. Peppas CRC Press, Boca Raton, FL;Netti, P.A., Shelton, J.C., Revell, P.A., Pirie, C., Smith, S., Ambrosio, L., Nicolais, L., Bonfield, W., (1993) Biomaterials, 14, p. 1098; Woerly, S., (1993) Biomaterials, 14, p. 1056; Peppas, N.A., (1996) Biomaterials Science an Introduction to Materials in Medicine-Part I, p. 60. , edited by B. D. Ratner, A. S. Hoffman, F. J. Schoen and J. E. Lemons Academic Press, London; Pascual, B., Castellano, I., Vázquez, B., Gurruchaga, M., Goñi, I., (1996) Polymer, 37, p. 1005; Mack, E.J., Okano, T., Kim, S.W., (1988) Hydrogels in Medicine and Pharmacy-Polymers, 2, p. 65. , edited by N. A. Peppas CRC Press, Boca Raton, FL; Karadag, E., Saraydin, D., Çetinkaya, S., Guven, O., (1996) Biomaterials, 17, p. 67; Kim, S.W., Bae, Y.H., Okano, T., (1992) Pharmaceut. Res., 9, p. 283; Blanco, M.D., García, O., Trigo, R.M., Teijon, J.M., Katime, I., (1996) Biomaterials, 17, p. 1061; Abusafieh, A., Siegler, S., Kalidingi, S.R., (1997) J. Biomed. Res., 38, p. 314; Norman, T.L., Kish, V., Blaha, J.D., Gruen, T.A., Hustosky, K., (1995) J. Biomed. Mater. Res., 29, p. 495; Yang, J., (1997) Biomaterials, 18, p. 1293; Lewis, G., Nyman, J.S., Trieu, H.H., (1997) J. Biomed. Mater. Res., 38, p. 221; Lewis, G., (1997) J. Biomed. Mater. Res., 38, p. 155; Domb, A.J., Manor, N., Elmalak, O., (1996) Biomaterials, 17, p. 411; Kost, J., Langer, R., (1988) Hydrogels in Medicine and Pharmacy-Properties and Applications, 3, p. 95. , edited by N. A. Peppas CRC Press, Boca Raton, FL; Lohmann, D., (1995) Macromol. Symp., 100, p. 25; Ogawa, Y., (1997) J. Biomater. Sci. Polymer Edn, 8, p. 391; Di Silvio, L., Gurav, N., Kayser, M.V., Braden, M., Downes, S., (1994) Biomaterials, 15, p. 931; Andreopoulos, A.G., (1994) Clin. Mater., 15, p. 691; Langer, R., (1995) MRS Bull., p. 18; Heller, J., (1996) Applications of Materials in Medicine and Dentistry-Part II, p. 346. , edited by B. D. Ratner, A. S. Hoffman, F. J. Schoen and J. E. Lemons Academic Press, London; Bastioli, C., (1994) Recycle'94 - Davos Global Forum and Exposition, , Switzerland, March; Bastioli, C., (1995) Degradadble Polymers-Principles and Applications, p. 112. , Chapman and Hall, London; Reis, R.L., Cunha, A.M., (1995) J. Mater. Sci. Mater. Med., 6, p. 786; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) Polym. Adv. Technol., 7, p. 784; Reis, R.L., Mendes, S.C., Cunha, A.M., Bevis, M.J., (1997) Polym. Int., 43, p. 347; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1997) Adv. Poly. Technol., 16, p. 263; Reis, R.L., Cunha, A.M., Bevis, M.J., (1997) Med. Plast. Biomateri., p. 46; Pereira, C.S., Gomes, M.E., Reis, R.L., Cunha, A.M., (1998) Foams, Emulsion and Cellular Materials, , edited by J. F. Sadoc and N. River NATO/ASI series, Kluwer Press, Dordrecht, in press; Reis, R.L., Cunha, A.M., (1998) Antec'98-Plastics on My Mind, , Society of Plastics Engieers, Atlanta, April/May in press; Reis, R.L., Cunha, A.M., (1998) Antec'98-Plastics on My Mind; Elvira, C., Levenfeld, B., Vázquez, B., San Román, J., (1996) J. Polym. Sci. A Polym. Chem., 34, p. 2783; Liso, P.A., Vázquez, B., Rebuelta, M., Hernáhz, M.L., Rotger, R., San, J., (1997) Biomaterials, 18, p. 15; Vázquez, B., Elvira, C., Levenfeld, B., Pascual, B., Goñi, I., Gurruchaga, M., Ginerba, M.P., San Róman, J., (1997) J. Biomed. Mater. Res., 34, p. 129; Vázquez, B., Elvira, C., San Román, J., Levenfeld, B., (1997) Polymer, 38, p. 4365; Castellano, I., Pascual, B., Vázquez, B., Goñi, I., Gurrruchaga, M., (1994) J. Appl. Polym. Sci., 54, p. 577; Jane, J., (1995) J.M.S. Pure Appl. Chem., A32, p. 751; Peppas, N.A., Korsmeyer, R.W., (1988) Medicine and Pharmacy-Properties and Applications, 3, p. 109. , edited by N. A. Peppas CRC Press, Boca Raton, FL; Saha, S., Pal, S., (1984) J. Biomed. Mater. Res., 18, p. 435; Lautenschlager, E.P., Moore, B.K., Schoenfeld, C.M., (1974) J. Biomed. Mater. Res. Symp., p. 185; Migiaresi, C., Fambri, L., Kolanik, J., (1994) Biomaterials, 15, p. 875; Topoleski, L.D.T., Ducheyne, P., Cuckler, J.M., (1993) Biomaterials, 14, p. 1165; Clarke, R.L., (1989) Biomaterials, 10, p. 494
Keywords: acrylic acid; alcohol; article; benzoyl peroxide; Biodegradation; bone cement; buffer; cellulose acetate; compression; Diffusion; drug delivery system; dynamics; fracture; free radical; hydrogel; infrared spectroscopy; Kinetics; low temperature; mechanical stress; oxidation reduction reaction; pH; poly(methyl methacrylate); Polymerization; priority journal; Scanning electron microscopy; Starch; tensile strength; Thermal analysis

Adsorptive Stripping Voltammetric Measurements of Chromium Accumulation in Mice Organs Using Mercury Film Microelectrodes - Pereira, M.C.; Pereira, M.L.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1997)
Chromium is the metallic species of most concern with the use of stainless steel implants. To study the distribution of chromium in mice organs with time, several animals were subcutaneously injected with 2.70 × 10
Cited By (since 1996): 19Export Date: 21 November 2012Source: ScopusCODEN: ELANELanguage of Original Document: EnglishCorrespondence Address: Sousa, J.P.; Inst. de Engenharia Biomédica, Depto. de Engenharia Química, Universidade do Porto, Praça do Coronel Pacheco, 1, P-4050 Porto, PortugalReferences: Katz, S.A., Salem, H., (1994) The Biological and Environmental Chemistry of Chromium, , VCH, Weinheim ch. 5;Black, J., (1988) J. Bone Joint Surg., 70 B, p. 517; Minski, M.J., Dobbs, H.S., (1980) Trace Element Analytical Chemistry in Medicine and Biology, p. 339. , (Eds: P. Bratter, P. Schramel), Walter de Gruyter, Berlin; Bartolozzi, A., Black, J., (1985) Biomaterials, 6, p. 2; Merritt, K., Fedele, C.D., Brown, S.A., (1992) Biomaterial-Tissue Interfaces, p. 10. , (Eds: P.J. Doherty et al), Elsevier, Amsterdam; Merritt, K., Brown, S.A., (1995) J. Biomed. Mater. Res., 29, p. 627; Katz, S.A., Salem, H., (1993) J. Appl. Toxicology, 13, p. 217; Polak, J.L., Turk, J., Frey, R., (1973) Prog. Allergy, 17, p. 145; Standeven, A.M., Wetterhahn, K.E., (1991) Chem. Res. Toxicol., 4, p. 616; Anderson, R.A., (1989) Sci. Total Environ., 86, p. 75; Lugowski, S., Smith, D.C., Van Loon, J.C., (1987) J. Biomed. Mater. Res., 21, p. 657; Subramanian, K.S., (1989) Metabolism of Minerals and Trace Elements in Human Disease, , (Eds: M. Abdulla et al), Smith-Gordon ch. 28; Minami, H., Zhang, Q., Itoh, H., Atsuya, I., (1994) Microchemical J., 49, p. 126; Veillon, C., Patterson, K.Y., Bryden, N.A., (1982) Clin. Chem., 28, p. 2309; Golimowski, J., Valenta, P., Nurnberg, H.W., (1985) Fresenius Z. Anal. Chem., 322, p. 315; Boussemart, M., Van Den Berg, C.M.G., Ghaddaf, M., (1992) Anal. Chim. Acta, 262, p. 103; Wang, J., Lu, J., Olsen, K., (1992) Analyst, 117, p. 1913; Olsen, K.B., Wang, J., Setiadji, R., Lu, J., (1994) Environ. Sci. Technol., 28, p. 2074; Pereira, M.C., Faria, J.L., Reis, M.L., Sousa, J.P., (1997) Electroanalysis, 9, p. 1; Pereira, M.C., Sousa, J.P., (1996) Portug. Electrochem. Acta, 14, p. 273; Pereira, M.C., Sousa, J.P., (1995) Portug. Electrochem. Acta, 13, p. 477; Miller, J.N., (1992) Analyst, 117, p. 1913; Van Den Berg, C.M.G., (1991) Anal. Chim. Acta, 250, p. 265; Merritt, K., Crowe, T.D., Brown, S.A., (1989) J. Biomed. Mater. Res., 23, p. 845; Yang, J., Black, J., (1989) Biomaterials, 23, p. 845; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci: Mater. Med., 6, p. 523
Keywords: Adsorptive stripping voltammetry; Biomaterials; Chromium; Microelectrodes

Apatite deposition on titanium surfaces - The role of albumin adsorption - Serro, A.P.; Fernandes, A.C.; Saramago, B.; Lima, J.; Barbosa, M.A. (BiomaterialsBIOMATERIALS, 1997)
Titanium implant surfaces are known to spontaneously nucleate apatite layers when in contact with simulated body fluids. However, adsorption of proteins may influence the process of apatite layer formation. In this study the role of bovine serum albumin (BSA) adsorption in the process of apatite deposition on titanium substrates is investigated. Deposition of calcium phosphate was induced by immersing titanium substrates in a Hank's balanced salt solution (HBSS) for times ranging from 1 to 23 days. The resulting substrates were studied by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), wettability measurements and electrochemical impedance determinations. All these methods indicate the presence of a calcium phosphate layer. The same procedure was repeated substituting HBSS with a solution of BSA in HBSS. Although SEM, EDS and electrochemical impedance spectra do not reveal the presence of an apatite layer, XPS analysis strongly indicates that the inhibition of apatite formation by BSA is only partial. The competition between BSA adsorption and apatite deposition seems to lead to a mixed film where the protein co-exists with calcium phosphate. Wettability studies suggest that this surface film is heterogeneous and porous, similar to the thicker films formed in albumin-free HBSS.Titanium implant surfaces are known to spontaneously nucleate apatite layers when in contact with simulated body fluids. However, adsorption of proteins may influence the process of apatite layer formation. In this study the role of bovine serum albumin (BSA) adsorption in the process of apatite deposition on titanium substrates is investigated. Deposition of calcium phosphate was induced by immersing titanium substrates in a Hank's balanced salt solution (HBSS) for times ranging from 1 to 23 days. The resulting substrates were studied by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), wettability measurements and electrochemical impedance determinations. All these methods indicate the presence of a calcium phosphate layer. The same procedure was repeated substituting HBSS with a solution of BSA in HBSS. Although SEM, EDS and electrochemical impedance spectra do not reveal the presence of an apatite layer, XPS analysis strongly indicates that the inhibition of apatite formation by BSA is only partial. The competition between BSA adsorption and apatite deposition seems to lead to a mixed film where the protein co-exists with calcium phosphate. Wettability studies suggest that this surface film is heterogeneous and porous, similar to the thicker films formed in albumin-free HBSS.
Cited By (since 1996): 72Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(97)00031-8PubMed ID: 9212191Language of Original Document: EnglishCorrespondence Address: Serro, A.P.; Centro de Quimica Estrutural, Complexo I, Instituto Superior Tecnico, Av. Rovisco Pais, 1096 Lisboa Codex, PortugalChemicals/CAS: alpha-tricalcium phosphate; Apatites; calcium phosphate, 10103-46-5; Calcium Phosphates; dicalcium phosphate anhydrous, 7757-93-9; Hanks Balanced Salt Solution; Isotonic Solutions; monocalcium phosphate; Serum Albumin, Bovine; tetracalcium phosphate; Titanium, 7440-32-6References: Sundgren, J.-E., Bodo, P., Lundstrom, I., Auger electron spectroscopic studies of the interface between human tissue and implants of titanium and stainless steel (1986) J. Colloid Interface Sci., 10, pp. 9-20;Hanawa, T., Ota, M., Characterization of surface film formed on titanium in electrolyte using XPS (1992) Appl. Surface Sci., 55, pp. 269-276; Sousa, S.R., Barbosa, M.A., Corrosion resistance of titanium cp in saline physiological solutions with calcium phosphate and proteins (1993) Clin. Mater., 14, pp. 287-294; Li, P., Ohtsuki, C., Kokubo, T., Nakanishi, K., Soga, N., De Groot, K., The role of hydrated silica, titania and alumina in inducing apatite on implants (1994) J. Biomed. Mater. Res., 28, pp. 7-15; Tanahashi, M., Yao, T., Kokubo, T., Apatite coating on organic polymers by a biomimetic process (1994) J. Am. Ceram. Soc., 77, pp. 2805-2808; Martin, R.I., Brown, P.W., Formation of hydroxy-apatite in serum (1994) J. Mater. Sci.: Mater. Med., 5, pp. 96-102; Malmsten, M., Ellipsometric studies of protein layers adsorbed at hydrophobia surfaces (1994) J. Colloid Interface Sci., 166, pp. 333-342; Oscarsson, S., Protein adsorption onto protein-covered silica-gels (1994) J. Colloid Interface Sci., 165, pp. 402-410; Baier, R.E., Meyer, J.R., Natella, R.R., Carter, J.M., Surface properties determine bioadhesive outcomes: Methods and results (1984) J. Biomed. Mater. Res., 18, pp. 337-355; Andrade, J.D., (1985) Surface and Interfacial Aspects of Biomedical Polymers, 2, pp. 1-80. , ed. J. D. Andrade. Plenum Press, New York; Van Der Vegt, W., Van Der Mei, H.C., Busscher, H.J., Interfacial free energies in protein solution droplets on FEP-Teflon by axisymmetric drop shape analysis by profile - IgG versus BSA (1993) J. Colloid Interface Sci., 156, pp. 129-136; Kipaldi, V.D., Lemons, J.E., Surface energy characterization of unalloyed titanium (1994) J. Biomed. Mater. Res., 28, pp. 1419-1425; Van Der Vegt, W., Van Der Mei, H.C., Busscher, H.J., A comparison of different approaches to calculate surface free energy of protein-coated substrata from measured contact angles of liquids (1994) Langmuir, 10, pp. 1314-1318; Cheng, P., Li, D., Boruvka, L., Rotenberg, Y., Neumann, A.W., Automation of axisymmetric drop shape analysis for measurements of interfacial tensions and contact angles (1990) Colloids Surfaces, 43, pp. 151-167; Cheng, P., Neumann, A.W., Computational evaluation of axisymmetric drop shape analysis - Profile (ADSA-P) (1992) Colloids Surfaces, 62, pp. 297-306; Barbosa, M.A., Electrochemical impedance studies on calcium phosphate-metal interfaces (1991) Bioceramics, 4, pp. 325-333. , ed. W. Bonfield, G. W. Hastings and K. E. Tanner. Butterworth-Heinemann, London; Ström, G., Carlsson, G., Wettability of kraft pulps -Effect of surface composition and oxygen plasma treatment (1993) Contact Angle, Wettability and Adhesion, pp. 475-491. , ed. K. L. Mittal. VSP, Utrecht; Good, G.R., Contact angle, wetting, and adhesion: A critical review (1992) J. Adhesion Sci. Technol., 6, pp. 1269-1302; Gomes, C.M., Fernandes, A.C., Almeida, B.S., The surface tension of cork from contact angle measurements (1993) J. Colloid Interface Sci., 156, pp. 195-201; Van Oss, C.J., Good, R.J., Chaudhury, M.K., The role of van der Waals and hydrogen bonds in hydrophobic interactions between biopolymers and low energy surfaces (1986) J. Colloid Interface Sci., 111, pp. 378-390; Absolom, D.R., Van Oss, C.J.A., Neumann, A.W., Determination of surface tensions of proteins. II. Surface tension of serum albumin, altered at the protein-air interface (1981) Biochim. Biophys. Acta, 670, pp. 74-78; Paynter, R.W., Ratner, B., The study of interfacial proteins and biomolecules by X-ray photoelectron spectroscopy (1985) Surface and Interfacial Aspects of Biomedical Polymers, 2, pp. 189-216. , ed. J. D. Andrade. Plenum Press, New York; Raider, S.I., Flitsch, R., Palmer, M.J., Oxide growth on etched silicon in air at room temperature (1975) J. Electrochem. Soc.: Solid State Sci. Technol., 122, pp. 413-418
Keywords: Adsorption; Albumin; Albumin adsorption; Animals; Apatite; Apatite deposition; Apatites; article; Binding Sites; Bovinae; bovine serum albumin; Calcium Compounds; calcium phosphate; Calcium phosphates; Cattle; Deposition; Electric Impedance; Electrochemical impedance; Energy dispersive spectroscopy; impedance; implant; Isotonic Solutions; Microscopy, Electron, Scanning; priority journal; Prostheses and Implants; Proteins; Scanning electron microscopy; Serum Albumin, Bovine; Spectrometry, X-Ray Emission; Substrates; Surface Properties; surface property; Surfaces; Tissue Preservation; Titanium; wettability; X ray photoelectron spectroscopy

Electrochemical and surface modifications on N +-ion implanted Ti-5Al-2.5Fe immersed in HBSS - Leitão, E.; Silva, R.A.; Barbosa, M.A. (Corrosion ScienceCorros. Sci., 1997)
The electrochemical behaviour of nitrogen ion-implanted Ti-5Al-2.5Fe was studied in HBSS-Hank's balanced salt solution, by open-circuit potential vs time and cyclic polarization techniques. Three fluences (10 15, 10 16 and 10 17 ions/cm 2) were used. All ion-implanted surfaces showed higher corrosion resistance than the non-implanted ones. The corrosion potential of the ion-implanted samples was more noble and their passivation current was lower than the non-implanted ones. X-ray photo-electron spectroscopy showed that the immersion of Ti-5Al-2.5Fe in HBSS produces a Ca- and P-rich surface layer. © 1997 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 21Export Date: 21 November 2012Source: ScopusCODEN: CRRSALanguage of Original Document: EnglishCorrespondence Address: Leitão, E.; INEB - Inst. de Engenharia Biomedica, Praça do Coronel Pacheco, 1, 4050, Porto, PortugalReferences: Tengvall, P., Lundström, I., (1992) Clinical Mater., 9, pp. 115-134;Seah, K.H.W., Chen, X., (1993) Corros. Sci., 34 (11), pp. 1841-1851; Sutherland, D.S., Forshaw, P.D., Allen, G.C., Brow, I.T., Williams, K.R., (1993) Biomaterials, 14 (12), pp. 893-899; Kasemo, B., (1983) J. of Prosthetic Dentistry, 49 (6), pp. 832-837; Ducheyne, P., Radin, S., Ishikawa, K., (1992) Bone-bonding Biomaterials, pp. 213-218. , edited by P. Ducheyne, T. Kokubo and C.A. van Blitterswijk, (Reed Heathcare Communications); Sundgreen, J.-E., Bodö, P., Lundström, I., (1986) J. Colloid Interface Sci., 110, pp. 9-20; Hanawa, T., Ota, M., (1991) Biomaterials, 12, pp. 767-774; Leitão, E., Barbosa, M.A., De Groot, K., (1995) J. Mater. Sci.: Mater. in Med., 6, pp. 849-852; Pavlov, P.V., (1983) Nucl. Inst. Meth. Phys. Res., 209-210, pp. 791-798; Sioshansi, P., (1984) Thin Solid Films, 118, pp. 61-71; Bernard, F., Dupuy-Philon, J., Bert, J., Remy, D., Meyer, B., Besse, J.L., (1995) Advances in Mater. Sci. and Implant Orthop. Surgery, pp. 195-206. , edited by R. Kossowsky and N. Kossovsky; Leitão, E., Sá, C., Silva, R.A., Barbosa, M.A., Ali, H., (1995) Corros. Sci., 37 (11), pp. 1861-1866; Hohmuth, K., Rauschenbach, B., (1985) Mater. Sci. Eng., 69, pp. 489-499; Rauschenbach, B., Kolitsch, A., (1983) Phys. Stat. Sol (A), 80, pp. 211-222; Rauschenbach, B., Kolitsch, A., Hohmuth, K., (1983) Phys. Stat. Sol (A), 80, pp. 471-482; Rauschenbach, B., (1991) Nucl. Inst. Meth. Phy. Res., B53, pp. 35-45; Dos Santos, C.A., Behar, M., De Souza, J.P., Baumvol, I.J.R., (1983) Nucl. Instrum. Methods, 209-210, pp. 907-912; Helmig, K., Rauschenbach, B., (1986) Phys. Stat. Sol. (B), 138, pp. k1-k6; Maüsli, P.A., Simpson, J.P., Burri, G., Steinemann, S.G., (1988) Advances in Biomater., 8, p. 305. , Implant Mater. In Biofunction, edited by C. de Putter, C.L. de Lange, K. de Groot and A.J.C. Lee; Maüsli, P.A., Bloch, P.R., Geret, V., Steinemann, S.G., (1986) Biological and Biomechanical Performance of Biomaterials, p. 57. , edited by P. Christel, A. Meunier and A.J.C. Lee; Sousa, S.R., Barbosa, M.A., (1993) Clinical Mater., 14, pp. 287-294; Orr, R.D., De Bruijn, J.D., Davies, J.E., (1992) Cells and Mater., 2 (3), pp. 241-245; Klein, C.A.P.T., Patka, P., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., (1994) Biomater., 15, pp. 146-150
Keywords: A. titanium alloys; B. EIS; B. XPS; C. passive films; Corrosion resistance; Cyclic polarization technique; Hank's balanced salt solution (HBSS); Ion implantation; nitrogen; Open circuit potential technique; Passivation; Passive films; Surface treatment; Titanium alloys; X ray photoelectron spectroscopy

Electrochemical and surface modifications on N +-ion-implanted 316L stainless steel - Leitão, E.; Silva, R.A.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1997)
The effect of nitrogen-ion implantation on the electrochemical behaviour of 316L stainless steel in a simulated physiological solution (HBSS-Hank's Balanced Salt Solution) was studied by open-circuit potential versus time and cyclic polarization techniques, with the aim of characterizing the surfaces and choosing the best nitrogen-ion fluence. Three fluences (10 15, 10 16 and 10 17 ions/cm 2) were used. The 10 16 ions/cm 2 N + fluence improves the corrosion resistance of the 316L stainless steel. The effect of nitrogen-ion implantation on the electrochemical behaviour of 316L stainless steel in a simulated physiological solution (HBSS-Hank's Balanced Salt Solution) was studied by open-circuit potential versus time and cyclic polarization techniques, with the aim of characterizing the surfaces and choosing the best nitrogen-ion fluence. Three fluences (10 15, 10 16 and 10 17 ions/cm 2) were used. The 10 16 ions/cm 2 N + fluence improves the corrosion resistance of the 316L stainless steel.
Cited By (since 1996): 32Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1018532900458Language of Original Document: EnglishCorrespondence Address: Leitao, E.; Instituto de Engenharia Biomedica, Praca do Coronel Pacheco 1, 4050 Porto, PortugalReferences: Seah, K.H.W., Chen, X., (1993) Corros. Sci., 34, pp. 1841-1851;Fraker, A.C., Ruff, A.W., Sung, P., Van Orden, A.C., Speck, K.M., (1983) Titanium Alloys in Surgical Implants, pp. 206-219. , ASTM STP 796, edited by H. A. Luckey and F. Kublei Jr; Nakayama, Y., Yamamuro, T., Kumar, P., Shimisu, K., Kotoura, Y., Oka, M., Kwafuku, J., Takashima, T., (1990) J. Appl. Biomater., 1, pp. 307-313; Puleo, D.A., Huh, W.W., (1995) J. Appl. Biomater., 6, pp. 109-116; Sundgreen, J.-E., Bodö, P., Lundström, I., (1986) J. Colloid Interface Sci., 110, pp. 9-20; Merrit, K., Brown, S.A., (1995) J. Biomedical Mater. Res., 29, pp. 627-633; Merrit, K., Brown, S.A., (1994) Tech Orthop., 8, pp. 228-236; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci. Mater. Med., 6, pp. 523-527; Johansson, C.B., Lausmaa, J., Röstlund, T., Thomsen, P., (1993) J. Mater. Sci. Mater. Med., 4, pp. 132-141; Bernard, F., Dupuy-Philon, J., Bert, J., Remy, D., Moyen, B., Besse, J.L., Advances in materials science and implant orthopaedic surgery (1995) NATO-ASI Series E: Applied Science, 24, pp. 195-206. , edited by R. Kossowsky and N. Kossowsky; Rauschenbach, B., (1991) Nucl. Instrum. Methods Phys. Res., B53, pp. 35-45; Rauschenbach, B., Kolitsch, A., Hohmuth, K., (1983) Phys. Status Solidi (A), 80, pp. 471-482; Howlett, C.R., Evans, M.D.M., Wildish, K.L., Kelly, J.C., Fisher, L.R., Francis, G.W., Best, D.J., (1993) Clin. Mater., 14, pp. 57-64; Howlett, C.R., Zreiqat, H., O'Dell, R., Noorman, J., Evans, P., Dalton, B.A., Mcfarland, C., Steele, J.G., (1994) J. Mater. Sci. Mater. Med., 5, pp. 715-722; Röstlund, T., Thomson, P., Bjursten, L.M., Ericson, L.E., (1990) J. Biomed. Mater. Res., 24, pp. 847-860; Leitão, E., Sá, C., Silva, R.A., Barbosa, M.A., Ali, H., (1995) Corros. Sci., 37, pp. 1861-1866; Barbosa, M.A., (1989) Portugaliae Electrochimica Acta, 7, pp. 567-590; Rauschenbach, B., Kolitsch, A., (1983) Phys. Status Solidi (A), 80, pp. 211-222; Rauschenbach, B., (1991) Nucl. Tracks Radiat. Meus., 19, pp. 943-946; Carbucicchio, M., Bardani, L., Tosto, S., (1981) J. Appl. Phys., 52, p. 4589; Hu, W.W., Herman, H., Clayton, C.R., Kozubowski, J., Kant, R.A., Hirvonen, J.K., Maccrone, R.K., Surface related mechanical properties of nitrogen implanted 1018 steel (1979) Proc. Ion Implantation Metallurgy, p. 92. , edited by C. M. Preece and J. K. Hirvonen AIME. Warrendale, Cambridge, MA; Dos Santos, C.A., Behar, M., De Souza, J.P., Baumvol, I.J.R., (1983) Nucl. Inustrum. Methods, 209-210, pp. 907-912; Sousa, S., Barbosa, M.A., (1991) J. Mater. Sci. Mater. Med., 2, pp. 19-26; Klein, C.A.P.T., Patka, P., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., (1994) Biomaterials, 15, pp. 146-150
Keywords: article; balanced salt solution; Composition effects; Corrosion; Corrosion resistance; Cyclic polarization technique; Electrochemical corrosion; electrochemistry; implantation; Ion implantation; limb prosthesis; nitrogen; Polarization; priority journal; prosthesis failure; Simulated physiological solutions; Solutions; Stainless steel; Stainless steel 316L; Surface Properties; Surface treatment; time

Electrochemical impedance spectroscopy of nitrogen- and carbon-sputter coated 316 L stainless steel - Leitão, E.; Silva, R.A.; Barbosa, M.A. (Corrosion ScienceCorros. Sci., 1997)
The effect of nitrogen and carbon sputter coatings on the electrochemical behaviour of 316 L stainless steel in a simulated physiological solution (Hank's Balanced Salt Solution) was studied by electrochemical impedance spectroscopy with the aim of characterizing the surfaces and choosing the best coating. Coatings with different thicknesses and structures were tested. The results showed that thicker sputter coatings produce surfaces with higher charge transfer resistance and lower interface capacities. This indicates that these materials probably owe their high corrosion resistance to the formation of more protective films. © 1997 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: CRRSALanguage of Original Document: EnglishCorrespondence Address: Leitão, E.; INEB - Inst. de Engenharia Biomedica, Praça do Coronel Pacheco, 1, 4050, Porto, PortugalReferences: Gristina, A.G., Naylor, P., Myrvik, Q., (1988) Medical Progress Through Technology, 14, pp. 205-224;Gomi, K., Davies, J.E., (1993) J. Biomedical Mater. Res., 27, pp. 429-431; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford J., Jr., Dean, D.D., Boyan, B.D., (1995) J. Biomedical Mater. Res., 29, pp. 389-401; Groessner-Schreiber, B., Tuan, R.S., (1992) J. of Cell Sc., 101, pp. 209-217; Peidl, R.D., Ramp, W.K., Nicholson, N.C., Kaisinger, K.K., Harrow, M.E., (1994) 20th Annual Meeting of the Society for Biomaterials, 11. , Boston, USA; Puleo, D.A., Holleran, L.A., Doremus, R.H., Bizios, R., (1991) J. Biomedical Mater. Res., 25, pp. 711-723; Vrouwenvelder, W.C.A., Groot, C.G., De Groot, K., (1993) J. Biomedical Mater. Res., 27, pp. 465-475; Hazan, R., Oron, U., (1993) J. of Orthopaedic Res., 11, pp. 655-663; De Bruijn, J.D., Flach, J.S., De Groot, K., Van Blitterswijk, C.A., Davies, J.E., (1993) Cells and Mater., 3, pp. 2115-2127; Röstlund, T., Thomsen, P., Bjursten, L.M., Ericson, L.E., (1990) J. Biomedical Mater. Res., 24, pp. 847-860; Bard, A.J., Faulkner, L.R., (1980) Electrochemical Methods, , John Wiley and Sons; Bundy, K.J., Dillard, J., Luedemann, R., (1993) Biomaterials, 14 (7), pp. 529-536; Leitão, E., Sá, C., Silva, R.A., Barbosa, M.A., Ali, H., (1995) Corros. Sci., 37, pp. 1861-1866; Garrido, A., Leitão, E., (1992) IMPFRA-electrochemical Impedance Software, , internal publication; (1993) Project BRITE/EURAM n°0477 Internal Report; Barbosa, M.A., (1991) Bioceramics, 4, pp. 325-333. , Edited by W. Bonfield, G.W. Hastings and K.E. Tanner; Sousa, S.R., Barbosa, M.A., (1993) Clinical Materials, 14, pp. 287-294
Keywords: A. Stainless steel; B. EIS; C. passive films; Carbon; Charge transfer; Coatings; Composition effects; Corrosion resistance; electrochemistry; Films; Hank's balanced salt solution; nitrogen; Passive films; Protective coatings; sodium chloride; Spectroscopy; Sputter deposition; Stainless steel; Surface phenomena

Iron Determination in Osteoblast-Like Cell Culture Medium by Adsorptive Cathodic Stripping Voltammetry with a Mercury Microelectrode - Morais, S.; Carvalho, G.S.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1997)
Mercury film microelectrodes were used to determine iron in osteoblast-like cell culture medium by performing adsorptive cathodic stripping voltammetry in the presence of catechol. The optimized analytical conditions are a catechol concentration of 5.00×10
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: ELANELanguage of Original Document: EnglishCorrespondence Address: Sousa, J.P.; Inst. de Engenharia Biomedica, Depto. de Engenharia Química, Universidade do Porto, Praça Coronel Pacheco, 1, 4050 Porto, PortugalReferences: Cigada, A., (1994) Proc. Symp. Compatibility of Biomedical Implants, 94 (15), pp. 185-192. , (Eds.: P. Kovacs, N.S. Istephanous), The Electrochemical Society, Pennington, NJ;Pohler, O.E.M., (1983) Biomaterials in Reconstrutive Surgery, p. 158. , C.V. Mosby, St. Louis; Black, J., Oppenheimer, P., Morris, D.M., Peduto, A.M., Clark, C.C., (1987) J. Biomed. Mater. Res., 21, p. 1213; Sunderman, F.W., Hopper, S.M., Swift, T., Rezuke, W.N., Ziebra, L., Highman, P., Edwards, B., Gossling, H.R., (1989) J. Orthop. Res., 7, p. 307; Traisnel, M., Maguer, D., Hildebrand, H.F., (1990) Clin. Mater., 5, p. 309; Moore, R.M., Hamburger, S., Jeng, L.J., Hamilton, P.M., (1991) J. Appl. Biomater., 2, p. 127; Henning, E.F., Raithel, H.J., Schaller, K.H., Dohler, J.R., (1992) J. Trace Elem. Electrolytes Health Dis., 6, p. 239; Brown, S.A., Zhang, K., Merritt, K., Payer, J.H., (1993) J. Biomed. Mater. Res., 27, p. 1007; Albore-Saavedra, J., Vuitch, F., Delgado, R., Wiley, E., Hagler, H., (1994) Am. Surg. Pathol., 18, p. 83; Buechel, F.F., Drucker, D., Jasty, M., Jiranek, W., Harris, W.H., (1994) Clin. Orthop. Related Res., 298, p. 202; Valenta, P., Rutzel, H., Nurnberg, H.W., Stoeppler, M., (1977) Z. Anal. Chem., 285, p. 25; Nurnberg, H.W., (1977) Electrochim. Acta, 22, p. 935; Nurnberg, H.W., (1978) Proc. Anal. Div. Chem. Soc., 15, p. 275; Golimowski, S.J., Valenta, P., Stoepper, M., Nurnberg, H.W., (1979) Talanta, 26, p. 649; Cox, J.A., Majda, M., (1980) Anal. Chim. Acta, 118, p. 271; Van Den Berg, C.M.G., Huang, Z.Q., (1984) J. Electroanal. Chem., 177, p. 269; Wang, J., Mahmoud, J.S., (1986) J. Electroanal. Chem., 208, p. 383; Van Den Berg, C.M.G., Nimmo, N., Abollino, O., Mentasti, E., (1991) Eleclroanalysis, 3, p. 477; Sousa, J.P., Morais, S., Pereira, M.C., Pereira, M.L., Carvalho, G.S., Barbosa, M.A., (1994) Biomaterials, 15, p. 821; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci.: Mater. Med., 6, p. 523; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci.: Mater. Med., 6, p. 56; Vilamitjana-Amedee, J., Bareille, R., Rouais, F., Caplan, A.I., Harmand, M.F., (1993) In Vitro Cell. Dev. Biol., 29 A, p. 699; Bizios, R., (1994) Biotechnol. Bioeng., 43, p. 582; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Arciola, C.R., Granchi, D., Savarino, L., (1994) Clin. Mater., 15, p. 173; Winter, G.D., (1974) J. Biomed. Mater. Res. Symp., 5, p. 11; De Vernejoul, M.C., Pointillart, A., Golenzer, C.C., Morieux, C., Bielakoff, J., Modrowski, D., Miravet, L., (1985) Metals in Bone, pp. 321-331. , (Ed: N.D. Priest), MTT Press Dordrecht; Pend, J., Jin, W., (1992) Anal. Chim. Acta, 264, p. 213; Van Den Berg, C.M.G., (1984) Anal. Chim. Acta, 164, p. 195; Maniatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tissue Res., 254, p. 317; Kotz, L., Henze, G., Kaiser, G., Pahlke, S., Veber, M., Tolg, G., (1979) Talanta, 26, p. 681; Huizenga, D.L., Rester, D.R., (1984) J. Electroanal. Chem., 164, p. 229; Capodaglio, G., Van Den Berg, C.M.G., Scarponi, G., (1987) J. Electroanal. Chem., 235, p. 275; Torrance, K., Gatford, C., (1986) Analyst, 111, p. 359; Wang, J., Lu, J., Olsen, K., (1992) Analyst, 117, p. 1913; Miller, J.N., (1991) Analyst, 116, p. 3; Morais, S., Sousa, J.P., Fernandes, H., Carvalho, G.S., (1994) Last Minute Posters Abstracts Book, 11th European Conference on Biomaterials, pp. 10-11. , Pisa, Italy; Lugowski, S., Smith, D.C., Van Loon, J.C., (1987) J. Biomed. Mater. Res., 21, p. 657
Keywords: Cell culture medium; Iron; Mercury film microelectrode

Nickel Determination in Osteoblast-Like Cell Culture Medium by Adsorptive Cathodic Stripping Voltammetry with a Mercury Microelectrode - Morais, S.; Carvalho, G.S.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1997)
The purpose of this study is to investigate the influence of nickel, which is an alloying element in commonly used metallic biomaterials, on the biomaterials mineralization process. An electrochemical method was developed to quantify this metal ion in osteoblast-like cell culture medium (OST) by performing adsorptive cathodic stripping voltammetry (CSV) with dimethylglyoxime (DMG) at a mercury film microelectrode (MFM). The optimized analytical conditions and the square-wave CSV parameters for the analysis are: DMG concentration: 5.00 × 10
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: ELANELanguage of Original Document: EnglishCorrespondence Address: Sousa, J.P.; Inst. de Engenharia Biomedica, Depto. de Engenharia Química, Universidade do Porto, Praça Coronel Pacheco, 1, 4050 Porto, PortugalReferences: Williams, D.F., (1981) Biomaterials and Biocompatibility: An Introduction, in Fundamental Aspects of Biocompatibility, 1. , CRC Press, Boca Raton, FL;Tsalev, D.L., Zaprianov, Z.K., (1983) Atomic Absorption Spectrometry in Occupational and Environmental Health Practice, 1. , CRC Press, Boca Raton, FL; Fishbein, L., Mehlman, M.A., (1987) Advances in Modern Environmental Toxicology, pp. 145-183. , CRC Press, Boca Raton, FL; Costa, M., (1989) Env. Health. Perspect., 81, p. 73; Ward, J., Thornbury, D.D., Lemons, J.., Dunham, W.., (1990) Clin. Orthoped., 252, p. 299; Florence, T.M., (1970) J. Electroanal. Chem., 27, p. 273; Batley, J.E., Florence, T.M., (1976) J. Electroanal. Chem., 72, p. 121; Wang, J., Zadeii, Z., (1988) J. Electroanal. Chem., 246, p. 297; Daniele, S., Baldo, M.A., Ugo, P., Mazzocchin, G., (1989) Anal. Chim. Acta, 219, p. 9; Daniele, S., Baldo, M.A., Ugo, P., Mazzocchin, G., (1989) Anal. Chim. Acta, 219, p. 19; Eskilsson, H., Haraldsson, C., Jagner, D., (1985) Anal. Chim. Acta., 175, p. 79; Economou, A., Fielden, P.R., (1993) Analyst, 118, p. 47; Wightman, R.M., Wipt, D.O., (1989) Voltammetry at Ultramicroelectrodes, pp. 335-336. , Ed: A.J. Bard, Marcel Dekker, New York; Pereira, M.C., Pereira, M.L., Sousa, J.P., (1995) Biomed. Lett., 52, p. 235; Sousa, J.P., Morais, S., Pereira, M.C., Pereira, M.L., Carvalho, G.S., Barbosa, M.A., (1994) Biomaterials, 15, p. 821; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci.: Mater. Med., 6, p. 523; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci.: Mater. Med., 6, p. 56; Maniatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tiss. Res., 254, p. 317; Morais, S., Sousa, J.P., Fernandes, H., Carvalho, G.S., (1994) Last Minute Posters Abstracts Book, 11th European Conference on Biomaterials, Pisa, Italy, pp. 10-11; Peng, J., Jin, W., (1992) Anal. Chim. Acta, 264, p. 213; Gunawardena, G., Hills, G., Montenegro, I., Scharifker, B., (1982) J. Electroanal. Chem., 138, p. 225; Milchev, A., Scharifker, B., Hills, G., (1981) J. Electroanal. Chem., 132, p. 277; Sousa, J.P., (1991), Ph.D. Dissertation, University of UtahBailey, F., Malinski, T., Kiechle, F., (1991) Anal. Chem., 63, p. 395; Wightman, R.M., (1981) Anal. Chem., 53, pp. 1125A; Turner, A.P.F., Karube, I., Wilson, G.S., (1987) Biosensors Fundamentals and Applications, , Oxford University Press, Oxford; Golas, J., Galus, Z., Osteryoung, J., (1987) Anal. Chem., 59, p. 389; Baranski, A.S., (1987) Anal. Chem., 59, p. 662; Kounaves, S.P., (1992) Anal. Chem., 64, p. 2998; Feinberg, J.S., Bowyer, W.J., (1993) Microchem. J., 47, p. 72; Kounaves, S.P., Deng, W., (1993) Anal. Chem., 65, p. 375; Bustin, D., Mesaros, S., Rievaj, M., Tomcik, P., (1995) Electroanalysis, 4, p. 7; Ostapczuk, P., Valenta, P., Nurnberg, H., (1986) J. Electroanal. Chem., 214, p. 51; Pihlar, B., Valenta, P., Nurnberg, H.W., (1981) Z. Anal. Chem., 307, p. 337; Gammelgaar, B., Andersen, J.R., (1985) Analyst, 110, p. 1197; Vos, L., Komy, Z., Reggers, G., Rockens, E., Van Grieken, R., (1986) Anal. Chim. Acta, 184, p. 271; Torrance, K., Gatford, C., (1985) Talanta, 32, p. 273; Braun, H., Metzgar, M., (1984) Z. Anal. Chem., 318, p. 321; Adeloju, S.B., Bond, A.M., Briggs, M.H., (1984) Anal. Chim. Acta, 164, p. 181; Wahdat, F., Neeb, R., (1985) Z. Anal. Chem., 320, p. 334; Kotz, L., Henze, G., Kaiser, G., Pahlke, S., Veber, R., Tolg, G., (1979) Talanta, 26, p. 681; Wurfels, M., Jackwerth, E., Stoeppler, M., (1989) Anal. Chim. Acta, 226, p. 17; Wurfels, M., Jackwerth, E., Stoeppler, M., (1989) Anal. Chim. Acta, 226, p. 31; Basu, B.J., Rajagopalan, S.R., (1992) Analyst, 117, p. 1623; Bond, A.M., Luscombe, D.L., (1986) J. Electroanal. Chem., 214, p. 21; Van Den Berg, C.M.G., (1991) Anal. Chim. Acta, 250, p. 265; Miller, J.N., (1991) Analyst, 116, p. 3; Wu, T.G., Wong, J.L., (1991) Anal. Chim. Acta, 246, p. 301; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., (1991) Bone and Mineral, 14, p. 27; Wehmeyer, K.R., Wightman, R.M., (1985) Anal. Chem., 57, p. 1989; Nurnberg, H.W., (1977) Electrochim. Acta, 22, p. 935
Keywords: Cell culture medium; Mercury film microelectrode; Nickel

Nickel Quantification in Mice Organs by Adsorptive Cathodic Stripping Voltammetry Using Mercury Microelectrodes - Pereira, M.C.; Faria, J.L.; Reis, M.L.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1997)
Mercury film microelectrodes (MFMs) were used to quantify trace levels of nickel accumulated in mice organs samples after dosing the mice with a physiological solution containing 150 ppm of Ni ions over a period of time, by performing adsorptive cathodic stripping square wave voltammetry (AdSWV). The residues obtained after digestion of the biological organs with nitric acid which affects the electrochemical response of Ni were investigated by XRD and IR spectrometry and found to be mainly composed by p-nitrobenzoic acid. Electrochemical conditions for the quantification of Niwith MFMs in the biological solutions were optimized. The electrochemical data compared favorably with that obtained by atomic absorption spectrometry.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: ELANELanguage of Original Document: EnglishCorrespondence Address: Sousa, J.P.; Inst. de Engenharia Biomedica, Depto. de Engenharia Química, Faculdade Engenharia da Univ. do P., Praça do Coronel Pacheco, 1, P-4050 Porto, PortugalReferences: Mark H.B., Jr., (1964) J. Electroanal. Chem., 7, p. 276;Crow, D.R., Rose, M.E., (1979) Electrochim. Acta, 24, p. 41; Smith, R.G., Windom, H.L., (1980) Anal. Chim. Acta, 113, p. 39; Cantwell, F.F., Nielsen, J.S., Hrudey, E., (1982) Anal. Chem., 54, p. 1498; Pearson, R.M., Siem, H.J., (1977) Anal. Chem., 49, p. 580; Basu, B.J., Rajagopalan, S.R., (1992) Analyst, 117, p. 1623; Wu, T., Wong, J.L., (1990) Anal. Chim. Acta, 235, p. 457; Flora, C., Nieboer, E., (1980) Anal. Chem., 52, p. 1013; Pihlar, B., Valenta, P., Nurnberg, H.W., (1986) J. Electroanal. Chem., 214, p. 157; Martell, A.E., Smith, R.M., (1977) Critical Stability Constants, 3. , Plenum Press, New York; Eriksrud, E., (1975) J. Electroanal. Chem., 60, p. 41; Zhang, H., Wollast, R., Vire, J., Patriache, G.J., (1989) Analyst, 114, p. 1597; Ostapczuk, P., Valenta, P., Nurnberg, H.W., (1986) J. Electroanal. Chem., 214, p. 51; Economou, A., Fielden, P.R., (1993) Analyst, 118, p. 47; Brett, C.M.A., Oliveira Brett, A.M.C.F., Pereira, J.L.C., (1991) Electroanalysis, 3, p. 683; Adeloju, S.B., Bond, A.M., Briggs, M.H., (1984) Anal. Chim. Acta, 164, p. 181; Wang, J., (1985) Stripping Analysis, , VCH, Deerfield Beach, FL; Bond, A.M., Fleischmann, M., Robinson, J., (1984) J. Electroanal. Chem., 172, p. 11; Ewing, A.C., Dayton, M.A., Wightman, R.M., (1981) Anal. Chem., 53, p. 1942; Montenegro, M.I., Queirós, M.A., Dashbach, J.L., (1991) Microelectrodes: Theory and Applications, , NATO-ASI, Kluwer Academic Publishers, Amsterdam, The Netherlands; Scharifker, B., Hills, G.J., (1981) J. Electroanal. Chem., 130, p. 81; Sousa, J.P., (1991), Ph. D. Thesis, University of UtahSousa, J.P., (1994) J. Electroanal. Chem., 372, p. 151; Sousa, J.P., Morais, S.B., Pereira, M.C., Pereira, M.L., Carvalho, G.S., Barbosa, M.A., (1994) Biomaterials, 15, p. 821; Sousa, J.P., Pereira, M.C., (1994) Portug. Electrochem. Acta, 12, p. 63; Wehmeyer, K.R., Wightman, R.M., (1985) Anal. Chem., 57, p. 1989; Kovacs, P., Istephanous, N.S., (1994) Compatibility of Biomedical Implants, , The Electrochemical Society, Pennington, NJ; Pereira, M.C., Sousa, J.P., (1995) Portug. Electrochem. Acta, 13, p. 477; Abreu, A.M., Tracana, R.B., Carvalho, G.S., Sousa, J.P., (1996) Biomed. Lett., 52, p. 133; Morais, S., Carvalho, G.S., Sousa, J.P., (1995) Portug. Electrochim. Acta, 13, p. 483; Griffiths, P.R., De Haseth, J.A., (1986) Fourier Transform Infrared Spectrometry, 83. , Chemical Analysis, (Eds: P.J. Elving, J.D. Winefordner) Wiley, New York; Lin-Vien, D., Colthup, N.B., Fateley, W.G., Grasselli, J.G., (1991) The Handbook of Infrared and Roman Characteristic Frequencies of Organic Molecules, , Academic Press, New York; Pereira, M.L., Pereira, M.C., Sousa, J.P., (1995) Biomed, Lett., 52, p. 235
Keywords: Adsorptive stripping voltammetry; Mice organs; Microelectrodes; Nickel

Amino acid and metal content of Crassostrea gigas shell infested by Polydora sp. in the prismatic layer insoluble matrix and blister membrane - Almeida, M.J.; Moura, G.; MacHado, J.; Coimbra, J.; Vilarinho, L.; Ribeiro, C.; Soares-Da-Silva, P. (Aquatic Living ResourcesAquatic Living Resour., 1996)
The spionid polychaete Polydora sp. can live and reproduce inside the oysters' shell, excavating a U-shaped burrow the central portion of which is filled with detritus and particles of dissolved shell. The oyster responds by secreting an organic layer, confining the worm, and later covering it with calcitostracum. This process creates a characteristic "mud blister". Crassostrea gigas were analysed for the organic matrix amino acid content and 14 metals of the whole shell of normal oysters and severely Polydora infested ones. Amino acid, DOPA and FT-Raman analyses were also performed on isolated membranes from the characteristic mud blister and on prismatic layer insoluble matrix (PLIM) of infested oysters, with the aim of detecting any differences between the two organic matrices. Membranes and PLIM composition differ from whole normal shell organic matrix by having lower aspartate and glycine and higher levels of virtually all hydrophobic amino acids, especially alanine. There are no significant differences between membranes and PLIM in the ratio of charged to non-polar amino acids, respectively 0.54 and 0.59. L-DOPA content is also similar in the two matrices with 0.45 (±0.18) and 0.57 (±0.30) ng.mg
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: ALREELanguage of Original Document: EnglishCorrespondence Address: Almeida, M.J.; Laboratório de Fisiologia Aplicada, Instituto de Ciências Biomédicas Abel Salazar, 4050 Porto, PortugalReferences: Allen, J.A., Manganese deposition on the shell of living molluscs (1960) Nature, 185, pp. 336-337;Beedham, G.E., Repair of the shell in species of Anodonta (1965) Proc. Zool. Soc. London, 145, pp. 107-125; Boggess, R.K., Martin, R.B., Copper chelation by DOPA, epinephrine and other catechols (1975) J. Am. Soc. Chem., 97, pp. 3076-3081; Brown, C.H., (1975) Structural Materials in Animals, , Wiley, New York; Bubel, A., An electron microscope study of periostracum repair in Mytilus edulis (1973) Mar. Biol., 20, pp. 235-244; Carriker, M.R., Swann, C.P., Prezant, R.S., Counts, C.L., Chemical elements in the aragonitic and calcitic microstructural groups of shell of the oyster Crassostrea virginica: A proton probe study (1991) Mar. Biol., 109, pp. 289-297; Catherine, M., Blateau, D., Mazurié, J., Le Bec, C., (1990) Anomalies des Coquilles D'huîtres Creuses Crassostrea Gigas Observées sur le Littoral Français en Mai-juin 1989, Dues au ver Polydora et aux Peintures Antisalissures., pp. 13-14. , Rapp. Int. Dir. Ressources Vivantes, IFREMER Nantes; Degens, E.T., Spencer, D.W., Parker, R.H., Paleobiochemistry of Molluscan shell proteins (1967) Comp. Biochem. Physiol., 79, pp. 553-579; Dorsett, D.A., The behavior of Polydora ciliata (Johnst.). Tube building and burrowing (1961) J. Mar. Biol. Assoc. U.K., 41, pp. 577-590; Felix, C.C., Sealy, R.C., Electron spin resonance characterization of radicals from 3-4-dihydroxyphenylalanine: Semiquinone anions and their metal chelates (1981) J. Am. Chem. Soc., 103, pp. 2831-2835; Galstoff, P.S., The American oyster Crassostrea virginica (Gmelin) (1964) Fish. Bull. U.S., p. 64; Gergely, A., Kiss, T., Coordination chemistry of L-DOPA and related ligands (1979) Met. Ions Biol. Syst., 9, pp. 143-172; Haigler, S., Boring mechanism of Polydora websteri inhabiting Crassostrea virginica (1969) Am. Zool., 9, pp. 821-828; Jones, G.M., Saleuddin, A.S.M., Cellular mechanisms of periostracum formation in Physa spp. (Mollusca: Pulmonata) (1978) Can. J. Zool., 56, pp. 2299-2311; Kawaguchi, T., Watabe, N., The organic matrices of the shell of the American oyster Crassostrea virginica Gmelin (1993) J. Exp. Mar. Biol. Ecol., 170, pp. 11-28; Kawaguti, S., Ikemoto, N., Electron microscopy on the mantle of a bivalve Musculus senhousia, during regeneration of shell (1962) Biol. J. Okayama Univ., 8, pp. 31-42; Krampitz, G., Drolshagen, H., Hotta, S., Simultaneous binding of calcium and bicarbonate by conchiolin of oyster shells (1983) Experiemia, 39, pp. 1104-1105; Laukner, G., Diseases of Mollusca: Bivalvia (1983) Diseases of Marine Animals, Vol. II, Bivalvia to Scaphopoda, 2, pp. 477-978. , Biologische Anstalt Helgoland, O. Kinne ed. Hamburg; Levitt, M., A simplified representation of protein conformation for rapid simulation of protein folding (1976) J. Mol. Biol., 104, pp. 59-108; Linderstrom-Lang, K., Duspiva, F., Studies in enzymatic histochemistry. XVI. the digestion of keratin by larvae of clothes moth (Tineola biselliela Humm.) (1936) C. R. Trav. Lab. Carlsberg, Ser. Chim., 21, pp. 1-82; Lowry, O.H., Rosebrough, N.J., Farr, A.L., Randall, R.J., Protein determination with the Folin phenol reagent (1951) J. Biol. Chem., 193, pp. 265-275; Martius, K.V., Schwarzhans, K.E., Preparation of the Mn (II) complex with 3,4-dihydroxyphenylalanine (DOPA) (1978) Z Naturforsch., 33 B, p. 124; Meenaakshi, V.R., Hare, P.E., Watabe, N., Wilbur, K.M., The chemical composition of the periostracum of the molluscan shell (1969) Comp. Biochem. Physiol., 29, pp. 611-620; Nozaki, Y., Tanford, C., The solubility of amino acids and two glycyl peptides in aqueous ethanol and dioxane solutions (1971) J. Biol. Chem., 246, pp. 2211-2217; Saleuddin, A.S.M., Petit, H.P., The mode of formation and the structure of the periostracum (1983) The Mollusca, 4, pp. 199-234. , K. M. Wilbur ed. Academic Press, New York; Sato-Okoshi, W., Okoshi, K., Microstructure of scallop and oyster shells infested with boring Polydora (1993) Nippon Suisan Gakkaishi, 59, pp. 1243-1247; Segar, D.A., Collins, J.D., Riley, J.P., The distribution of the major and some minor elements in marine animals. Part II (1971) Molluscs. J. Mar. Biol. Assoc. U.K., 51, pp. 131-136; Swinehart, J.H., Smith, K.W., Iron and manganese deposition in the periostraca of several bivalve molluscs (1979) Biol. Bull., 156, pp. 369-381; Travis, D.F., Gonsalves, M., Comparative ultrastructure and organization of the prismatic region of two bivalves and its possible relation to the chemical mechanism of boring (1969) Am. Zool., 9, pp. 635-661; Tsujii, T., An electron microscopic study of the mantle epithelial cells of Anodonta sp. during shell regeneration (1976) The Mechanisms of Mineralization in the Invertebrates and Plants, pp. 339-353. , N. Watabe, K. M. Wilbur eds. Univ. South Carolina Press, Columbia; Vovelle, J., Sclérotisation et minéralisation des structures squellettiques chez les Mollusques (1974) Haliotis, 2, pp. 133-165; Waite, J.H., Evidence for the mode of sclerotization in a molluscan periostracum (1977) Comp. Biochem. Physiol., 58 B, pp. 157-162; Waite, J.H., Quinone-tanned scleroproteins (1983) The Mollusca, 1, pp. 467-504. , K. M. Wilbur ed. Academic Press, New York; Waite, J.H., Andersen, S.O., 3,4-dihydroxyphenyl-alanine in an insoluble shell protein of Mytilus edulis (1978) Biochem. Biophys. Acta, 541, pp. 107-114; Wheeler, A.P., Rusenko, K.W., Swift, D.M., Sikes, C.S., Regulation of in vitro and in vivo CaCO 3 crystallization by fractions of oyster shell organic matrix (1988) Mar. Biol., 98, pp. 71-80; Zottoli, R.A., Carriker, M.R., Burrow morphology, tube formation and microarchitecture of shell dissolution by the spionid polychaete Polydora websteri (1974) Mar. Biol., 27, pp. 307-316
Keywords: Amino acids; Crassostrea gigas; Metals; Polydora sp.; Shell organic matrix

Characterization of apatite layer formation on P 2O 5-CaO, P 2O 5-CaO- Na 2O, and P 2O 5-CaO-Na - Jha, L.J.; Santos, J.D.; Knowles, J.C. (Journal of Biomedical Materials ResearchJ. BIOMED. MATER. RES., 1996)
P 2O 5-based glass hydroxyapatite (HA) composites denoted HA-2 oxide, HA-3 oxide, and HA-4 oxide, were immersed in Hank's balanced salt solution for a period of 1, 2, 3, and 4 weeks at 37°C in nonagitated condition for in vitro evaluation. A surface layer was precipitated on the composites that was analyzed using scanning electron microscopy (SEM), X-ray photoelecton spectroscopy, and thin film X-ray diffractometry (TF-XRD). SEM micrographs showed complete coverage of the composite surface by crystallites after immersion of 1 week in the solution, which grew thicker with respect to immersion time. The binding energies measured by XPS indicated apatite formation and the presence of carbonate on the composite surface, showing the newly formed layer was a carbonated apatite. Confirmation of the formed apatite layer was obtained by TF-XRD. 2O 5-based glass hydroxyapatite (HA) composites denoted HA-2 oxide, HA-3 oxide, and HA-4 oxide, were immersed in Hank's balanced salt solution for a period of 1, 2, 3, and 4 weeks at 37°C in nonagitated condition for in vitro evaluation. A surface layer was precipitated on the composites that was analyzed using scanning electron microscopy (SEM), X-ray photoelectron spectroscopy, and thin film X-ray diffractometry (TF-XRD). SEM micrographs showed complete coverage of the composite surface by crystallites after immersion of 1 week in the solution, which grew thicker with respect to immersion time. The binding energies measured by XPS indicated apatite formation and the presence of carbonate on the composite surface, showing the newly formed layer was a carbonated apatite. Confirmation of the formed apatite layer was obtained by TF-XRD.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(199608)31:4<481::AID-JBM7>3.0.CO;2-HPubMed ID: 8836844Language of Original Document: EnglishCorrespondence Address: Jha, L.J.; IRC in Biomedical Materials, Queen Mary and Westfield College, Mile End Road, London E1 4NS, United KingdomChemicals/CAS: HydroxyapatitesReferences: Hyakuna, K., Yamamuro, T., Kotoura, Y., Oka, M., Kokubo, T., Kushitani, H., Surface reactions of calcium phosphate ceramics to various solutions (1990) J. Biomed. Mater. Res., 24, pp. 471-488;Ebisawa, Y., Kokubo, T., Ohura, K., Yamamuro, T., Bioactivity of CaO·SiO 2-based glasses: In vitro evaluation (1990) J. Mater. Sci.: Mater. Med., 1, pp. 239-244; Kokubo, T., Kushitani, H., Ohtsuki, C., Sakka, S., Yamamuro, T., Chemical reaction of bioactive glass and glass ceramics with a simulated body fluid (1992) J. Mater. Sci.: Mater. Med., 3, pp. 79-83; Li, P., Yang, Q., Zhang, F., Kokubo, T., The effect of residual glassy phase in a bioactive glass-ceramic on the formation of its surface apatite layer in vitro (1992) J. Mater. Sci.: Mater. Med., 3, pp. 452-456; Ohtsuki, C., Aoki, Y., Kokubo, T., Yamamuro, T., Nakamura, T., Characterization of apatite layer formed on bioactive glass-ceramic A-W (1992) Bioceramics, 5, pp. 87-94. , T. Yamamuro, T. Kokubo, and T. Nakamura (eds.), Kokunshi Kankokai, Japan; Kokubo, T., Kushitani, H., Ohtsuki, C., Sakka, S., Effects of ions dissolved from bioactive glass-ceramic on surface apatite formation (1993) J. Mater. Sci.: Mater. Med., 4, pp. 1-4; Kohri, M., Miki, K., Waite, D., Nakajima, H., Okabe, T., In vitro stability of biphasic calcium phosphate ceramics (1993) Biomaterials, 14, pp. 299-304; Andersson, O.H., Kangasniemi, I., Calcium phosphate formation at the surface of bioactive glass in vitro (1991) J. Biomed. Mater. Res., 25, pp. 1019-1030; Kokubo, T., Kushitani, H., Sakka, S., Kitsugi, T., Yamamuro, T., Solutions able to reproduce in vivo surface-structure changes in bioactive glass-ceramic A-W (1990) J. Biomed. Mater. Res., 24, pp. 721-734; Santos, J.D., Knowles, J.C., Hastings, G.W., Bonfield, W., "Sintered hydroxyapatite compositions and method for the preparation thereof," British Patent No. 9,213,774.4 (1993)Santos, J.D., Reis, R.L., Knowles, J.C., Hastings, G.W., Monteiro, F.J., Microstructural characterisation of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Santos, J.D., Knowles, J.C., Monteiro, F.J., Hastings, G.W., Development of a glass reinforced hydroxyapatite with enhanced mechanical properties: Physical properties and in vitro studies (1992) Bioceramics, 5, pp. 35-41. , T. Yamamuro, T. Kokubo, and T. Nakamura (eds.), Kokunshi Kankokai, Japan; Knowles, J.C., Abrahams, I., Bonfield, W., Effect of reinforcing glass composition on phase transformation and crystallographic parameters in hydroxyapatite (1993) Bioceramics, 6, pp. 191-196. , P. Ducheyne and D. Christiansen (eds.), Butterworth Heinemann, New York; Knowles, J.C., Bonfield, W., Development of a glass reinforced hydroxyapatite with enhanced mechanical properties. The effect of glass composition on mechanical properties and its relationship to phase changes (1993) J. Biomed. Mater. Res., 27, pp. 1591-1598; Burnie, J., Gilchrist, T., Controlled release glass (C.R.C.) - A new biomaterial (1983) Ceramics in Surgery, pp. 169-176. , P. Vincenzini (ed.), Elsevier, Amsterdam; Santos, J.D., Jha, L.J., Monteiro, F.J., Study of surface modifications by x-ray photoelectron spectroscopy on glass reinforced hydroxyapatite composites in a simulated physiological solution (1995) Biomaterials, 16, pp. 521-526; Rehman, I., Hench, L.L., Bonfield, W., Comparison of hydroxycarbonate apatite layers on bioactive glasses with human bone (1993) Bioceramics, 6, pp. 123-128. , P. Ducheyne and D. Christiansen (eds.), Butterworth Heinemann, New York; Landis, W.J., Martin, J.R., X-ray photoelectron spectroscopy applied to gold-decorated mineral standards of biological interest (1984) J. Vac. Sci. Technol., A2, p. 1108; Swift, P., Adventitious carbon - The panacea for energy referencing? (1982) Surface Interface Anal., 4, pp. 47-51; Clark, D.T., Thomas, H.R., Applications of ESCA to polymer chemistry. XVII. Systematic investigation of the core levels of single homopolymers (1978) J. Polym. Sci., Polym. Chem. Ed., 16, pp. 791-820; Verhoeven, J.A., Van Doveren, H., An XPS investigation of the interface of methane, ethyne, ethene, and ethane with barium surface (1982) Surface Sci., 123, pp. 369-383
Keywords: Apatite; article; binding affinity; Biomaterials; bone strength; Calcium Compounds; Carbonates; Ceramic materials; Characterization; chemical composition; Composite materials; Crystallites; electron microscopy; glass; Glass hydroxyapatite composites; Hank balanced salt solution; hydroxyapatite; Hydroxyapatites; immersion; Microscopy, Electron, Scanning; Molecular Structure; Oxides; prosthesis material; Scanning electron microscopy; scanning tunneling microscopy; Spectrum Analysis; Thin film X ray diffractometry; Thin films; X ray diffraction; X ray diffraction analysis; X ray photoelectron spectroscopy; X-Ray Diffraction

Effect of hydroxyapatite thickness on metal ion release from Ti6Al4V substrates - Sousa, S.R.; Barbosa, M.A. (BiomaterialsBIOMATERIALS, 1996)
The electrochemical dissolution behaviour of Ti6Al4V alloy coated with hydroxyapatite (HA) by plasma spraying was studied in Hank's balanced salt solution (HBSS) and compared with that of polished and grit-blasted passivated surfaces. Two different nominal thicknesses of HA (50 and 200 μm) were used. Taking a polished passivated surface as reference, grit blasting of the substrate increased the electrical charge used in the oxidation of Ti6Al4V alloy at constant potential, as a result of increased surface area. However, only HA coatings with a thickness of 200 μm were capable of reducing the charge to values lower than those measured for polished surfaces. Electrochemical impedance spectroscopy has also shown that only 200 μm thick coatings are effective in reducing the oxidation rate of the substrate. Furthermore, in potentiostatic experiments the 50 μm thick coating detached from the substrate, which did not occur with the 200 μm thick coating. However, after 6 months immersion in HBSS, detachment occurred in some regions of both coatings. No titanium, aluminium or vanadium were detected in solution by electrothermal atomic absorption spectroscopy. These data indicate that HA is an effective barrier to metal ion release, even for the thinner coatings, due to formation of metal phosphates or to incorporation of metal ions in the HA structure.The electrochemical dissolution behaviour of Ti6Al4V alloy coated with hydroxyapatite (HA) by plasma spraying was studied in Hank's balanced salt solution (HBSS) and compared with that of polished and grit-blasted passivated surfaces. Two different nominal thicknesses of HA (50 and 200 μm) were used. Taking a polished passivated surface as reference, grit blasting of the substrate increased the electrical charge used in the oxidation of Ti6Al4V alloy at constant potential, as a result of increased surface area. However, only HA coatings with a thickness of 200 μm were capable of reducing the charge to values lower than those measured for polished surfaces. Electrochemical impedance spectroscopy has also shown that only 200 μm thick coatings are effective in reducing the oxidation rate of the substrate. Furthermore, in potentiostatic experiments the 50 μm thick coating detached from the substrate, which did not occur with the 200 μm thick coating. However, after 6 months immersion in HBSS, detachment occurred in some regions of both coatings. No titanium, aluminium or vanadium were detected in solution by electrothermal atomic absorption spectroscopy. These data indicate that HA is an effective barrier to metal ion release, even for the thinner coatings, due to formation of metal phosphates or to incorporation of metal ions in the HA structure.
Cited By (since 1996): 62Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/0142-9612(96)89655-4PubMed ID: 8938233Language of Original Document: EnglishCorrespondence Address: Sousa, S.R.; INEB, Praca do Coronel Pacheco 1, 4050 Porto, PortugalChemicals/CAS: Alloys; Biocompatible Materials; Durapatite, 1306-06-5; titanium alloy (TiAl6V4), 12743-70-3; Titanium, 7440-32-6References: Barbosa, M.A., Electrochemical impedance studies on calcium phosphate-metal interfaces (1991) Bioceramics, 4, pp. 325-333. , Bonfield W, Hastings GW, Tanner KE, eds. London: Butterworth-Heinemann;Sousa, S.R., Barbosa, M.A., Electrochemistry of AISI 316L stainless steel in calcium phosphate and protein solutions (1991) J Mater Sci: Mater Med, 2, pp. 19-26; Sousa, S.R., Barbosa, M.A., Corrosion resistance of titanium cp in saline physiological solutions with calcium phosphate and proteins (1993) Clin Mater, 14, pp. 287-294; Li, P., De Groot, K., Calcium phosphate formation within sol-gel prepared titania in vitro and in vivo (1993) J Biomed Mater Res, 27, pp. 1495-1500; Li, P., Kangasniemi, I., De Groot, K., Bonelike hydroxyapatitc induction by a gel-derived titania and a titanium substrate (1994) J Am Ceram Soc, 77, pp. 1307-1312; Ducheyne, P., Healy, K.E., The effect of plasma-sprayed calcium phosphate ceramic coatings on the metal ion release from porous titanium and cobalt-chromium alloys (1988) J Biomed Mater Res, 22, pp. 1137-1163; Weng, J., Liu, X., Zhang, X., Li, X., Thermal decomposition of hydroxyapatite structure induced by titanium and its dioxide (1994) J Mater Sci Lett, 13, pp. 159-161; Castro Ribeiro, C., Barbosa, M.A., Influence of metal ions on the dissolution behaviour of hydroxyapatite (1991) Bioceramics, 4, pp. 145-153. , Bonfield W, Hastings GW, Tanner KE, eds. Butterworth-Heinemann; ASTM G61-86, standard test method for: Conducting cyclic potentiodynamic polarization measurements for localized corrosion susceptibility of iron, nickel, or cobalt based alloys (1989) Annual Book of ASTM Standards, pp. 345-361. , 03.02. Philadelphia, PA: American Society for Testing and Materials; ASTM G 31-72 e1, standard practice for: Laboratory immersion corrosion testing of metals (1989) Annual Book of ASTM Standards, pp. 176-186. , 03.02. Philadelphia, PA: American Society for Testing and Materials; Barbosa, M.A., Surface layers and the reactivity of metallic implants (1992) Biomaterials - Hard Tissue Repair and Replacement, pp. 257-283. , Muster D et al. ed. Amsterdam: Elsevier Science Publishers BV; Rivero, D.P., Fox, J., Skipor, A.K., Urban, R.M., Galante, J.O., Calcium phosphate-coated porous titanium implants for enhanced skeletal fixation (1988) J Biomed Mater Res, 22, pp. 191-201; Oonishi, H., Yamamoto, M., Ishimaru, H., The effect of hydroxyapatite coating on bone growth into porous titanium alloy implants (1989) J Bone Joint Surg, 71 B, pp. 213-216; Bourne, R.B., Rorabeck, C.H., Burkar, B., Kirk, P.G., Ingrowth surfaces - Plasma spray coating to titanium alloy hip replacements (1994) Clin Orthop Rel Res, 298, pp. 37-46; Oonishi, H., Noda, T., Ito, S., Effect of hydroxyapatite coatings on bone growth into porous titanium alloy implants under loaded conditions (1994) J Appl Biomater, 5, pp. 23-37; Moroni, A., Caja, V.L., Egger, E.L., Trinchese, L., Chao, E.Y.S., Histomorphometry of hydroxyapatite coated and uncoated porous titanium bone implants (1994) Biomaterials, 15, pp. 926-930; Bloebaum, R.D., DuPont, J.A., Osteolysis from a press-fit hydroxyapatite-coated implant (1993) J Arthroplasty, 8, pp. 195-202; Bloebaum, R.D., Beeks, D., Dorr, L.D., Savory, C.G., DuPont, J.A., Hofmann, A.A., Complications with hydroxyapatite particulate separation in total hip arthroplasty (1994) Clin Orthop, 298, pp. 19-26; Klein, C.P.A.T., Patka, P., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., Long-term in vivo study of plasma-sprayed coatings on titanium alloys of tetracalcium phosphate, hydroxyapatite and α-tricalcium phosphate (1994) Biomaterials, 15, pp. 146-160; Reis, R.L., Monteiro, F.J., Hastings, G.W., Stability of hydroxyapatite plasma-sprayed coated Ti-6Al-4V under cyclic bending in simulated physiological solutions (1994) J Mater Sci: Mater Med, 5, pp. 457-462; Wang, B.C., Lee, T.M., Chang, E., Yang, C.Y., The shear strength and the failure mode of plasma-sprayed hydroxyapatite coating to bone: The effect of coating thickness (1993) J Biomed Mater Res, 27, pp. 1315-1327; Tranquilli Leali, P., Merolli, A., Palmacci, O., Gabbi, C., Cacchiolo, A., Gonizzi, G., Evaluation of different preparations of plasma-spray hydroxyapatite coating on titanium alloy and duplex stainless steel in the rabbit (1994) J Mater Sci: Mater Med, 5, pp. 345-349
Keywords: Absorption spectroscopy; Alloys; Aluminum; article; Atomic spectroscopy; balanced salt solution; Bioactive coatings; Biocompatible Materials; Biomaterials; Calcium Compounds; Dissolution; Durapatite; Electric charge; Electrochemical dissolution; Electrochemical impedance spectroscopy; electrochemistry; Electrothermal atomic absorption spectroscopy; Hank balanced salt solution; hydroxyapatite; Ion release; Ions; metal ion; Metal ion release; Metal phosphates; Microscopy, Electron, Scanning; Oxidation; Plasma spraying; potentiometry; priority journal; Spectrophotometry, Atomic; Spectroscopy; Substrates; thickness; Thickness effect; Time Factors; Titanium; Titanium alloys; vanadium

Fracture toughness of hydroxyapatite reinforced with P 2O 5-CaO glasses containing Na 2O, K 2O and MgO - Silva, P.L.; Santos, J.D.; Knowles, J.C.; Silva, R.F.; Monteiro, F.J. (Transactions of the Annual Meeting of the Society for Biomaterials in conjunction with the International Biomaterials SymposiumTrans Annu Meet Soc Biomater Int Biomater Symp, 1996)
Calcium phosphate materials are widely used in biomedical applications but their poor strength and brittleness limit their use in load bearing applications. To improve their mechanical properties, hydroxyapatite (HA) ceramics were reinforced with P 2O 5-CaO based glasses with additions of Na 2+, Mg 2+ and K + oxides. A composite chemical composition that approaches the inorganic part of bone chemical composition was obtained using HA with calcium phosphate-based glasses. Fracture toughness was significantly enhanced by glass additions, and the decrease in fracture toughness at 1300 and 1350 °C was attributed to grain growth since it significantly increased with sintering temperature.
Conference code: 45651Export Date: 21 November 2012Source: ScopusCODEN: TAMSELanguage of Original Document: EnglishCorrespondence Address: Silva, P.L.; INEB, Porto, Portugal
Keywords: Biomaterials; Bone; Composition effects; Fracture toughness; glass; Grain growth; hardness; Hydroxyapatites; Lime; Magnesia; Phosphate minerals; Potassium compounds; Sodium compounds; Thermal effects

Granules of osteoapatite and glass-reinforced hydroxyapatite implanted in rabbit tibiae - Afonso, A.; Santos, J.D.; Vasconcelos, M.; Branco, R.; Cavalheiro, J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
Granules of a modified hydroxyapatite, glass-reinforced hydroxyapatite composite and commercial hydroxyapatite were implanted in rabbit tibiae. Histological studies were carried out after 1 and 2 months implantation periods using light and fluorescence microscopy. A much higher percentage of bone contact was developed for both the glass-reinforced hydroxyapatite composite and the modified hydroxyapatite when compared to commercial hydroxyapatite (89-91% versus 66%) after 2 months implantation. The mechanism of bone formation and growth around implants is discussed in terms of the influence of elements incorporated into these novel materials which are commonly found in bone tissues, such as Na, K and Mg, and the presence of a soluble β-tricalcium phosphate phase in the microstructure of the composite.
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Afonso, A.; Faculty of Dental Medicine, University of Porto, Rua Dr Roberto Frias, 4200 Porto, PortugalChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; magnesium, 7439-95-4; potassium, 7440-09-7; sodium, 7440-23-5References: Ravaglioli, A., Krajewski, A., (1992) Bioceramics-materials, Properties and Applications, p. 100. , Chapman & Hall, London;Cranin, A.N., Ronen, E., Puntoff, R.S.H., Tobim, G., Dibeling, J.B., (1988) J. Biomed. Mater. Res., 22, p. 1165; De Groot, K., Klein, C.P.A.T., (1990) "Handbook of Bioactive Ceramics", Vol. II-Calcium Phosphate and Hydroxylapatite Ceramics, 2, p. 3. , edited by T. Yamamuro CRC Press, Boston; Hollinger, J.O., Schmitz, J.P., Mizgala, J.W., Hassler, C., (1989) J. Biomed. Mater. Res., 23, p. 17; Cavalheiro, J., Branco, R., Vasconcelos, M., (1991) Proceedings of the 4th International Conference on Bioceramics, p. 205. , edited by W. Bonfield, G. W. Hastings and K. E. Tanner, London, UK Butterworth-Heinemann, Oxford; Santos, J.D., Reis, R.L., Knowles, J.C., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Nery, E.B., Legeros, R.Z., Lynch, K.L., Kalbleisch, J., (1988) J. Dent. Res., 67, p. 178; Ellinger, R.F., Nery, E.B., Lynch, K.L., (1986) Int. J. Period. Restor. Dent., 3, p. 223; Legeros, R.Z., Daculsi, G., (1990) "Handbook of Bioactive Ceramics", Vol. II-Calcium Phosphate and Hydroxylapatite Ceramics, 2, p. 17. , edited by T. Yamamuro CRC Press, Boston
Keywords: animal experiment; animal tissue; article; Bone; Bone formation; bone growth; Calcium Compounds; calcium phosphate; Composite materials; Fiber reinforced materials; glass; Glass fibers; Glass reinforced hydroxyapatite; Granular materials; histology; hydroxyapatite; implant; Implants (surgical); Magnesium; Microstructure; Modified hydroxyapatite; nonhuman; Optical microscopy; ossification; Osteoapatite; Oxides; Phosphates; Physiological models; potassium; priority journal; rabbit; Rabbit tibiae; Sodium; tibia; X ray diffraction analysis

In vitro calcium phosphate formation on SiO 2-Na 2O-CaO-P 2O 5 glass reinforced hydroxyapatite composite: A study by XPS analysis - Santos, J.D.; Jha, L.J.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
In-vitro apatite layer formation on the surface of a newly developed glass reinforced hydroxyapatite composite was characterized using X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) equipped with energy dispersive X-ray analysis (EDXA). After 1 week soaking in an acellular simulated body fluid the composite surface was entirely covered by a Ca, P-layer, suggesting a bioactive behaviour. XPS binding energy results revealed that this surface layer was a carbonated and non- stoichiometric apatite with Ca/P ratio of 1.3. This apatite layer was composed of very fine needle-like crystallites. Comparative studies on a commercially available hydroxyapatite showed that a similar apatite layer was also formed on its surface.In-vitro apatite layer formation on the surface of a newly developed glass reinforced hydroxyapatite composite was characterized using X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) equipped with energy dispersive X-ray analysis (EDXA). After 1 week soaking in an acellular simulated body fluid the composite surface was entirely covered by a Ca, P-layer, suggesting a bioactive behaviour. XPS binding energy results revealed that this surface layer was a carbonated and non-stoichiometric apatite with Ca/P ratio of 1.3. This apatite layer was composed of very fine needle-like crystallites. Comparative studies on a commercially available hydroxyapatite showed that a similar apatite layer was also formed on its surface.
Cited By (since 1996): 42Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; FEUP, Rua dos Bragas, 4099-Porto Codex, PortugalChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8References: Ducheyne, P., (1987) J. Biomed. Mater. Res.: Appl. Biomater., 21 (A2), p. 219;Hench, L.L., (1989) J. Biomed. Mater. Res., 23, p. 685; Hench, L.L., (1991) J. Amer. Ceram. Soc., 7, p. 1487; Jarcho, M., (1988) Bioceramics 1, p. 57. , edited by H. Oonishi, H. Aoki and K. Sawai Ishiyaku Euro America, Tokyo; De Groot, K., (1980) Biomaterials, 1, p. 47; Blitterswijk, C.A.V., Koerten, H.K., Grote, J.J., (1986) Biological and Biomechanical Performance of Biomaterials, p. 27. , edited by P. Cristel, A. Meunier and A. J. C. Lee Elsevier Science Publishers, Amsterdam; Ono, K., Yamamuro, T., Nakamura, T., Kokubo, T., Kotoura, Y., (1988) J. Biomed. Mater. Res., 22, p. 869; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , Japanese Association of Apatite Science (JAAS), Takayama Press System Centre Co., Inc; Manabe, A., Shigematsu, M., Kobayashi, S., (1987) High Tech Ceramics, p. 63. , edited by P. Vincenzini Elsevier Science Publishers, Amsterdam; Kitsugi, T., Yamamuro, T., Nakamura, T., Kokubo, T., Ono, M., (1987) J. Biomed. Mater. Res., 21, p. 1109; Kokubo, T., Ito, S., Shigematsu, M., Sakka, S., Yamamuro, T., (1985) J. Mater. Sci. Mater. Med., 20, p. 2001; Mestral, F., Drew, R.L.A., (1989) J. Eur. Ceram. Soc., 5, p. 47; Burnie, J., Gilchrist, T., Kobayashi, S., (1983) Ceramics in Surgery, p. 169. , edited by P. Vincenzini Elsevier Science Publishers, Amsterdam; Andersson, O.H., Liu, G., Karlsson, K.H., Niemi, L., Juhanoja, J., (1990) J. Mater. Sci. Mater. Med., 1, p. 219; Knowles, J.C., Rehman, I., Bonfield, W., (1994) Bioceramics 7, p. 85. , edited by O. H. Andersson, R. P. Happonen and A. Yli-Urpo Butterworth Heinemann, Turku, Finland; Santos, J.D., Reis, R.L., Knowles, J.C., Hastings, G.W., Monteiro, F.J., (1994) Biomaterials, 15, p. 5; Santos, J.D., Knowles, J.C., Monteiro, F.J., Hastings, G.W., (1992) Bioceramics 5, p. 35. , edited by T. Yamamuro, T. Kokubo and T. Nakamura Kokunshi Kankokai, Kyoto; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1985) J. Mater. Sci. Mater. Med., 6, p. 448; Wilson, J., Low, S., (1992) J. Appl. Biomater., 3, p. 123; Oonishi, H., Kushitani, S., Yasukawa, E., Hench, L.L., Wilson, J., Tsuji, E., Sugihara, T., (1994) Bioceramics 7, p. 139. , edited by O. H. Andersson, R.-P. Happonen and A. Yli-Urpo, Butterworth Heinemann, Turku, Finland; Neo, M., Nakamura, T., Yamamuro, T., Ohtsuki, C., Kokubo, T., Bando, Y., (1992) J. Biomed. Mater. Res., 26, p. 1419; Hyakuna, K., Yamamuro, T., Kotoura, Y., Kokubo, T., Kushitani, H., (1990) J. Biomed. Mater. Res., 24, p. 471; Kokubo, T., Kushitani, H., Sakka, S., Kitsugi, T., Yamamuro, T., (1990) J. Biomed. Mater. Res., 24, p. 721; Santos, J.D., Jha, L.J., Monteiro, F.J., (1995) Biomaterials, 16, p. 521; Li, P., Ohtsuki, C., Kokubo, T., Nakanishi, K., Soga, N., Nakamura, T., Yamamuro, T., (1993) J. Appl. Biomater., 4, p. 221; Neo, M., Kotani, S., Fujita, Y., Yamamuro, T., Bando, Y., Ohtsuki, C., Kokubo, T., (1992) J. Biomed. Mater. Res., 26, p. 255; Li, P., Yang, Q., Zhang, F., Kokubo, T., (1992) J. Mater. Sci. Mater. Med., 3, p. 452; Kokubo, T., Kushitani, H., Kitsugi, T., Yamamuro, T., (1988) Bioceramics 1, p. 157. , edited by T. Yamamuro, T. Kokubo and T. Nakamura Kokunshi Kankokai, Kyoto; Landis, W.J., Martin, J.R., (1984) J. Vac. Sci. Technol., A2, p. 1108; Andersson, O.H., Kangasniemi, I., (1991) J. Biomed. Mater. Res., 25, p. 1019; Verhoeven, J.A.T., Van Doveren, H., (1982) Surf. Sci., 123, p. 369; Rehman, I., Hench, L.L., Bonfield, W., (1994) Bioceramics 7, p. 123. , edited by O. H. Andersson, R. P. Happonen and A. Yli-Urpo Butterworth Heinemann, Turku, Finland; Turner, N.H., Murday, J.S., Ramaker, D.E., (1980) Anal. Chem., 52, p. 84
Keywords: article; Binding energy; Biocompatibility; Biodegradation; biomaterial; Calcium; calcium phosphate; Characterization; Composite materials; Composition; Energy dispersive x ray analysis; glass; Glass reinforced hydroxyapetite composite; hydroxyapatite; implant; In vitro calcium phosphate formation; Ionic concentration; molecular interaction; Nucleation; Phosphates; phosphorus; priority journal; Scanning electron microscopy; Surfaces; X ray analysis; X ray photoelectron spectroscopy

Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts - Carvalho, G.S.; Castanheira, M.; Diogo, I.; Abreu, A.M.; Sousa, J.P.; Loon, J.A.; Van Blitterswijk, C.A. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
Fibroblasts from normal human skin were cultured for a period of 21 days in the absence or in the presence of metal ions. The effects of stainless steel (SS) corrosion products were compared to the effects of iron, chromium and nickel ions used either separately (Fe, Cr, or Ni solutions) or combined (Fe+Cr+Ni solution). At several periods of time (4, 7, 14 and 21 days) the cell cultures were analysed for the following parameters: (a) metal ion accumulation by atomic absorption spectrometry; (b) cell morphology and viability by the neutral red assay; (c) cell proliferation by DNA assessment, and enzyme activity by both (d) MTT reduction and (e) acid phosphatase activity. Results showed that SS-corrosion products and the corresponding metal ions combined at the same concentrations, Fe+Cr+Ni solution, had opposite effects on fibroblast cultures. In fact, SS-corrosion products caused no apparent effects on cell morphology nor on cell proliferation whereas Fe+Cr+Ni solution stimulated both neutral red uptake and cell proliferation. The enzymatic assays showed that SS-corrosion products caused inhibition of both MTT reduction and acid phosphatase activity in contrast to Fe+Cr+Ni solution which stimulated their activity. Furthermore, in all biological parameters studied, a strong association was observed between the effects of Fe+Cr+Ni solution and Cr alone, suggesting that Cr was the metal ion mostly involved in the stimulatory effects of the combined solution.Fibroblasts from normal human skin were cultured for 21 days in the absence, or presence, of metal ions. The effects of stainless steel (SS) corrosion products were compared to the effects of iron, chromium, and nickel ions used either separately or combined. At different periods of time, the cell cultures were analyzed for the following parameters: metal ion accumulation by atomic absorption spectrometry; cell morphology and viability by the neutral red assay; cell proliferation by DNA assessment; and enzyme activity by both MTT reduction and acid phosphatase activity. Results show that SS-corrosion products and the corresponding metal ions combined at the same concentrations, Fe+Cr+Ni solution, have opposite effects on fibroblast cultures.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Carvalho, G.S.; INEB-Instituto Engenharia Biomedica, Portugal Universidade do Minho, Praca Coronel Pacheco, 1, 4000 Porto, PortugalChemicals/CAS: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide, 298-93-1; acid phosphatase, 9001-77-8, 9025-88-1; chromium, 16065-83-1, 7440-47-3; DNA, 9007-49-2; iron, 14093-02-8, 53858-86-9, 7439-89-6; neutral red, 553-24-2; nickel, 7440-02-0; stainless steel, 12597-68-1References: Pohler, O.E.M., (1983) Biomaterials in Reconstructive Surgery, p. 158. , C.V. Mosby, St. Louis;Galante, J.O., Lemons, J., Spector, M., Wilson Jr., P.D., Wright, T.M., (1991) J. Orthop. Res., 9, p. 760; Henning, E.F., Raithel, H.J., Schaller, K.H., Döhler, J.R., (1992) J. Trace Elem. Electrolytes Health Dis., 6, p. 239; Maloney, W.J., Smith, R.L., Castro, F., Schurman, J., (1993) J. Bone Joint Surg., 75 A, p. 835; Jorgensen, T.J., Munno, F., Mitchell, T.G., Hungerford, D., (1983) Clin. Orthop., 176, p. 124; Jones, L.C., Hungerford, D.S., (1987) Trans Orthop. Res. Soc., 32, p. 317; Stulberg, B.N., Watson, J.T., Shull, S.L., Merritt, K., Crowe, T.D., Stulberg, S.D., Guidry, C.H., (1987) Trans Orthop. Res. Soc., 33, p. 314; Sunderman Jr., F.W., Hopfer, S.M., Swift, T., Rezuke, W.N., Ziebka, L., Highman, P., Edwards, B., Gossling, H.R., (1989) J. Orthop. Res., 7, p. 307; Merritt, K., Brown, S.A., Sharkey, N.A., (1984) J. Biomed. Mater. Res., 18, p. 991; Brown, S.A., Farnsworth, L.J., Merritt, K., Crowe, T.D., (1988) Biomed. Mater. Res., 22, p. 321; Merritt, K., Crowe, T.D., Brown, S.A., (1989) J. Biomed. Mater. Res., 23, p. 845; Merritt, K., Margevicius, R.W., Brown, S.A., (1992) J. Biomed. Mater. Res., 26, p. 1503; Brown, S.A., Zhang, K., Merritt, K., Payer, J.H., (1993) J. Biomed. Mater. Res., 27, p. 1007; Pereira, M.L., Silva, A., Tracana, R., Carvalho, G.S., (1994) Cytobios, 77, p. 73; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci. Mater. Med., 6, p. 523; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci. Mater. Med., 6, p. 56; Bravo, I., Sousa, S.R., Carvalho, G.S., Barbosa, M., (1992) Advances in Biomaterials, p. 7. , edited by P. J. Doherty et al. Elsevier, Amsterdam; Vrouwenvelder, W.C.A., Groot, C.G., DeGroot, K., (1993) J. Biomed. Mater. Res., 27, p. 465; Ciapetti, G., Cenni, E., Pratelli, L., Pizzoferrato, A., (1993) Biomaterials, 14, p. 359; Martin, A., Clynes, M., (1991) In Vitro Cell. Dev. Biol., 27 A, p. 183; Borenfreund, E., Puerner, J.A., (1983) J. Tissue Culture Methods, 9, p. 7; Hansen, M.B., Nielsen, S.E., Berg, K., (1989) J. Immunol. Methods, 119, p. 203; Rosdy, M., Grisoni, B., Claus, L.C., (1991) Biomaterials, 12, p. 511; Van Sliedregt, A., Radder, A.M., De Groot, K., Van Blitterswijk, C.A., (1992) J. Mater. Sci. Mater. Med., 3, p. 365; Caughman, W.F., Caughman, G.B., Shiflett, R.A., Rueggeberg, F., Schuster, G.S., (1991) Biomaterials, 12, p. 737; Carvalho, G.S., Bravo, I., (1993) J. Mater. Sci. Mater. Med., 4, p. 366; Harmand, M.F., Bordenave, L., Bareille, R., Naji, A., Jeandot, R., Rouais, F., Ducassou, D., (1991) J. Biomater. Sci. Polymer Edn., 2, p. 67; Katz, A., Feldman, M., Eisenbach, L., (1992) J. Immunol. Methods, 149, p. 117; Naji, A., Harmand, M.F., (1990) J. Biomed. Mater. Res., 24, p. 861; Mosmann, T., (1983) J. Immunol. Methods, 65, p. 55; Berridge, M.V., Tan, S., (1993) Arch. Biochem. Biophys., 303, p. 474
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; Absorption spectroscopy; Acid phosphatase; article; atomic absorption spectrometry; Atomic spectroscopy; Bioassay; Cell culture; Cell morphology; cell proliferation; cell structure; cell viability; Chromium; controlled study; Corrosion; Corrosion products; cytology; DNA; Enzymatic assays; Enzyme Activation; enzyme activity; Enzyme inhibition; fibroblast; human; human cell; Ions; Iron; metal; Metal ion accumulation; Metal salts; Metals; neutral red; Nickel; priority journal; Salts; Skin; skin fibroblast; Stainless steel; Steel corrosion

Potentiometric Determination of Total and Ionized Calcium in Osteoblast-Like Cell Culture Medium - Morais, S.; Carvalho, G.S.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1996)
The effect of the ionic strength and composition of solutions in the direct potentiometric determination of total and ionized calcium content using a calcium selective electrode was investigated. In the presence of a constant complexation buffer (CCB), the addition of sodium chloride and sodium bicarbonate causes a decrease in the limit of detection of the potentiometric response. When the procedure was tested in osteoblast-like cell culture medium no electrode interferences or method interferences were observed by the presence of proteins, i.e., the total and ionized calcium in this medium can be measured by potentiometric means.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: ELANELanguage of Original Document: EnglishCorrespondence Address: Sousa, J.P.; Inst. de Engenharia Biomédica, Faculdade de Engenharia, Universidade do Porto, Praça Coronel Pacheco, 1, P-4050 Porto, PortugalReferences: Nernst, W., (1886) Z. Phys. Chem., 2, p. 613;Nernst, W., (1889) Z. Phys. Chem., 4, p. 129; Morf, W.E., (1981) The Principle of Ion-Selective Electrodes and of Membrane Transport, , Elsevier, Amsterdam; Hulanicki, A., Trojanowicz, M., (1974) Anal. Chim. Acta, 68, p. 155; Anker, P., Wieland, E., Ammann, D., Dohner, R.E., Asper, R., Simon, W., (1981) Anal. Chem., 53, p. 1970; Manzoni, A., Premoli, P., (1985) Methodology and Clinical Applications of Ion-Selective Electrodes, pp. 131-136. , (Eds: A. H. J. Maas, A. B. T. J. Boink, N. E. L. Saris, R. Sprokholt, P. D. Wimberley), Radiometer, Copenhagen; Hulanicki, A., Lewandowski, R., Michalska, A., Lewenstam, A., (1990) Anal. Chim. Acta, 233, p. 269; Morais, S., Sousa, J.P., Fernandes, H., Carvalho, G.S., (1994) 11th European Conference on Biomaterials, Pisa, pp. 10-11. , Last Minute Posters Abstracts Book, European Society for Biomaterials; Ruzicka, J., Tjell, J.C., (1969) Anal. Chim. Acta, 47, p. 475; Ross, J.W., (1967) Science, 15, p. 1378; Rechnitz, G.A., Hseu, T.M., (1969) Anal. Chem., 41, p. 111; Oreskez, I., Hirsch, C., Douglas, K.S., Kupfer, S., (1968) Clin. Chim. Acta, 21, p. 203; Recomendations for Nomenclature of Ion-Selective Electrodes (1994) Pure Appl. Chem., 66, p. 2527; Ringbom, A., (1963) Complexation in Analytical Chemistry, , Interscience, New York; Russell Instruction Manual of Calcium Electrode Model 93-3209; Baudet, S., (1994) Methods in Cell Biology, pp. 93-113. , Academic Press, New York; Scharff, O., (1979) Anal. Chim. Acta, 109, p. 291
Keywords: Cell culture medium; potentiometry; Total and ionized calcium

Reinforcement of hydroxyapatite by adding P 2O 5-CaO glasses with Na 2O, K 2O and MgO - Santos, J.D.; Silva, P.L.; Knowles, J.C.; Talal, S.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
Commercial hydroxyapatite was reinforced by adding small amounts (2 and 4 wt%) of P 2O 5-based glasses during its sintering process. The composites prepared had a chemical composition closely related to the mineral part of bone tissues in terms of trace elements usually detected, such as Na, K and Mg. X-ray diffraction analysis (XRD) showed that the glass reinforced-HA composites were composed of a HA matrix and variable amounts of tricalcium phosphate phase, depending on sintering temperature and glass composition. These composites were shown to have much higher biaxial bending strength than sintered HA, 107 MPa for Ha/2% of 35P 2O 5-35CAO-10Na 2O-10K 2O-10MgO glass composite and 28 MPa for sintered HA. The presence of β-tricalcium phosphate in the microstructure of the composites is an important factor in the reinforcement process. Commercial hydroxyapatite was reinforced by adding small amounts (2 and 4 wt%) of P 2O 5-based glasses during its sintering process. The composites prepared had a chemical composition closely related to the mineral part of bone tissues in terms of trace elements usually detected, such as Na, K and Mg. X-ray diffraction analysis (XRD) showed that the glass reinforced-HA composites were composed of a HA matrix and variable amounts of tricalcium phosphate phase, depending on sintering temperature and glass composition. These composites were shown to have much higher biaxial bending strength than sintered HA, 107 MPa for Ha/2% of 35P 2O 5-35CaO-10Na 2O-10K 2O-10MgO glass composite and 28 MPa for sintered HA. The presence of β-tricalcium phosphate in the microstructure of the composites is an important factor in the reinforcement process.
Cited By (since 1996): 49Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; Dept. of Metallurgical Engineering, FEUP, University of Porto, Rua dos Bragas, 4099 Porto Codex, PortugalChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; magnesium oxide, 1309-48-4, 1317-74-4References: Barney, V.C., Levin, M.P., Adams, D.F., (1986) J. Perio Dont., 57, p. 764;Legeros, R.Z., (1988) Adv. Dent. Res., 2, p. 164; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, p. 165. , Takayama Press System Center, JAAS, Tokyo; Ducheyne, P., (1987) J. Biomed. Mater. Res. Appl. Biomater., 21, p. 219; Heughbaert, J.C., Bonel, G., (1986) Biological and Biomechanical Performance of Biomaterials, p. 9. , edited by P. Christel, A. Meunier and A. J. C. Lee Elsevier Science Publishers B.V., Amsterdam; Ellis, L.G., Nelson, D.G.A., Featherstone, J.D.B., (1988) J. Biomed. Mater. Res., 22, p. 541; Raemdonck, W.V., Ducheyne, P., Meester, P.D., (1984) Metal and Ceramic Biomaterials, p. 143. , edited by P. Ducheyne and G. W. Hashi CRC Press, Boca Raton, FL; Shors, E.C., Holmes, R.E., (1993) An Introduction to Bioceramics, p. 181. , edited by L. L. Hench and J. Wilson World Scientific, Hong Kong; Rey, C., (1990) Biomaterials, 11, p. 14; Evans, G., Behiri, J., Currey, J., Bonfield, W., (1990) J. Mater. Sci. Mater. Med., 1, p. 38; Rey, C., Frèche, M., Heughebaert, M., Heughebaert, J.C., Lacout, J.L., Vignoles, M., Bioceramics 4, London, 1991, p. 57. , edited by W. Bonfield, G. W. Hastings and K. E. Tanner (Butterworth-Heinemann, London); With, G., Van Dijk, H., Hattu, N., Prijs, K., (1981) J. Mater. Sci., 16, p. 1592; Akao, M., Aoki, H., Kato, K., (1981) J. Mater. Sci., 16, p. 809; Santos, J., Knowles, J., Reis, R., Monteiro, F., Hastings, G., (1994) Biomaterials, 15, p. 5; Soltesz, U., Richter, H., Kienzler, R., (1987) High Technology Ceramics, p. 110. , Elsevier Science Publishers, B.V., Amsterdam; (1971) Determination Micrographique de la Grosseur du Grain Ferritique ou Austénitique des Aciers; Daculsi, G., LeGeros, R.G., Nery, E., Lynch, K., Kerebel, B., (1989) J. Biomed. Mater. Res., 23, p. 883
Keywords: article; Bending strength; Bone; chemical composition; Composite materials; Composition; Composition effects; glass; Glass composition; Glass reinforced hydroxapatite composite; hydroxyapatite; implant; Magnesium Oxide; metal oxide; Microstructure; molecular dynamics; Phosphates; potassium derivative; priority journal; Sintering; Sintering temperature; sodium derivative; Thermal effects; Trace Elements; Tricalcium phosphate phase; X ray diffraction

Sintering effects in a glass reinforced hydroxyapatite - Knowles, J.C.; Talal, S.; Santos, J.D. (BiomaterialsBIOMATERIALS, 1996)
Glass was incorporated into hydroxyapatite (HA) to act as a sintering aid in order to improve the mechanical properties. The glass was added at 2 and 4 wt% and the powders compacted uniaxially. The compacts were sintered at a variety of temperatures (1200, 1250, 1300 and 1350°C) and the effects of the glass addition and the firing temperature were studied to determine their effects on the sintering process. It was found that the glass promoted some phase changes, related to the amount of glass added to the composite. At 1200 and 1250°C, some β-tricaicium phosphate (TCP) was found with the residual being HA. However, at 1300 and 1350°C, both β- and α-TCP were formed. The 4 wt% addition, as expected, promoted higher levels of secondary phases in the composite. The flexural bend strength (FBS) showed high values and also significant differences dependent on the amount of glass added. A 2 wt% addition gave a gradual increase in FBS with temperature. With a 4 wt% addition there was an increase in FBS, but above 1300°C there was a rapid decrease. These effects were mirrored in the linear shrinkage. Both the linear shrinkage and the FBS results were attributed to both the phase changes occurring and also change in grain size with increasing firing temperature.Glass was incorporated into hydroxyapatite (HA) to act as a sintering aid in order to improve the mechanical properties. The glass was added at 2 and 4 wt% and the powders compacted uniaxially. The compacts were sintered at a variety of temperatures (1200, 1250, 1300 and 1350°C) and the effects of the glass addition and the firing temperature were studied to determine their effects on the sintering process. It was found that the glass promoted some phase changes, related to the amount of glass added to the composite. At 1200 and 1250°C, some β- tricalcium phosphate (TCP) was found with the residual being HA. However, at 1300 and 1350°C, both β- and α-TCP were formed. The 4 wt% addition, as expected, promoted higher levels of secondary phases in the composite. The flexural bend strength (FBS) showed high values and also significant differences dependent on the amount of glass added. A 2 wt% addition gave a gradual increase in FBS with temperature. With a 4 wt% addition there was an increase in FBS, but above 1300°C there was a rapid decrease. These effects were mirrored in the linear shrinkage. Both the linear shrinkage and the FBS results were attributed to both the phase changes occurring and also change in grain size with increasing firing temperature.
Cited By (since 1996): 39Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/0142-9612(96)87287-5PubMed ID: 8830972Language of Original Document: EnglishCorrespondence Address: Knowles, J.C.; Eastman Dental Institute, Queen Mary and Westfield College, Mile End Road, London E1 4NS, United KingdomChemicals/CAS: Durapatite, 1306-06-5References: Currey, J.D., (1984) The Mechanical Adaptations of Bones, , Princeton University Press;Brown, W.E., Chow, L., Chemical composition of bone mineral (1976) Ann Res Mater Sci, 6, pp. 213-226; Glimcher, M.J., Recent studies of the mineral phase in bone and its possible linkage to the organic matrix by protein bound phosphate conds (1984) Phil Trans R Soc Land, B304, pp. 479-508; Cook, S.D., Thomas, K.A., Kay, J.F., Jarcho, M., Hydroxyapatite-coated porous titanium for use as an orthopaedic biologic attachment system (1980) Clin Orthop, 230, pp. 303-312; Patka, P., Den Otter, G., De Groot, K., Driessen, A.A., Reconstruction of large bone defects with calcium phosphate ceramics. An experimental study (1985) Neth J Surg, 37, p. 38; Wolford, L.M., Wardrop, R.W., Hartog, J.M., Coralline porous hydroxyapatite as a bone graft substitute in orthognathic surgery (1987) J Oral Maxillofac Surg, 45, pp. 1034-1042; Santos, J.D., Morrey, S., Hastings, G.W., Monteiro, F.J., The production and characterisation of a hydroxyapatite ceramic material (1991) Bioceramics, Vol 4. Proceedings of the 4th International Symposium on Ceramics in Medicine, 4, pp. 71-78. , Bonfield W, Hastings GW, Tanner KE, eds. London: Butterworth Heinemann; Dörre, E., Dawihl, W., Ceramic hip endoprostheses (1980) Mechanical Properties of Biomaterials, pp. 113-127. , Hastings GW, Williams DF, eds. New York: Wiley; Murray, M.G.S., Ponton, C.B., Marquis, P.M., Emulsion processing of hydroxyapatite (1992) Bioceramics, Vol 4. Proceedings of the 4th International Symposium on Ceramics in Medicine, 4, pp. 15-22. , Kyoto: Kobunshi Kankokai; Puajindanetr, S., Best, S.M., Bonfield, W., Characterisation and sintering of precipitated hydroxyapatite (1994) Br Ceram Trans, 93 (3), pp. 96-99; Knowles, J.C., Bonfield, W., Development of a glass reinforced hydroxyapatite with enhanced mechanical properties. The effect of glass composition on mechanical properties and its relationship to phase changes (1993) J Biomed Mater Res, 27, pp. 159-1598; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15 (1), pp. 5-10; Knowles, J.C., Development of hydroxyapatite with enhanced mechanical properties: Effect of high glass additions on mechanical properties and phase stability of sintered hydroxyapatite (1994) Br Ceram Trans, 93 (3), pp. 100-103; Ruys, A.J., Wei, M., Sorrell, C.C., Dickson, M.R., Brandwood, A., Milthorpe, B.K., Sintering effects on the strength of hydroxyapatite (1995) Biomaterials, 16, pp. 409-415; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions. Structure and properties of the composites (1995) J Mater Sci Mater Med, , to be published; Soltesz, U., Ritcher, H., Keinzler, R., (1987) High Tech Ceramics, p. 110. , Vincenzini P, ed. Amsterdam: Elsevier; Laugier, M.T., New formula for indentation toughness in ceramics (1987) J Mater Sci Lett, 6, pp. 355-356; Knowles, J.C., Abrahams, I., Bonfield, W., Effect of reinforcing glass composition on phase transformation and crystallographic parameters in hydroxyapatite (1993) Bioceramics, 6, pp. 191-196. , Ducheyne P, Christiansen D, eds. Butterworth-Heinemann
Keywords: article; Bending strength; Biomaterials; calcium phosphate; Chemistry, Physical; Durapatite; glass; Glass reinforced hydroxyapatite; Grain growth; hydroxyapatite; priority journal; Sintering; Sintering aid; temperature; tensile strength; Tricalcium phosphate; X-Ray Diffraction

Computerized fetal heart rate analysis in labour based on 2-s sampling. Can it proceed with confidence? [1] - Bernardes, J.; Garrido, A.; Chang, A.; Sahota, D.S.; Reed, N.N.; James, D.K.; Mohajer, M.P. (European Journal of Obstetrics Gynecology and Reproductive BiologyEUR. J. OBSTET. GYNECOL. REPROD. BIOL., 1995)
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: EOGRAdoi: 10.1016/0301-2115(95)02215-SPubMed ID: 8674558Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Instituto Engenharia Biomedica, Praca Coronel Pacheco 1, 4000 Porto, Portugal
Keywords: computer analysis; Computers; Female; Fetal monitoring; fetus; fetus heart rate; Heart Rate, Fetal; human; labor; Labor, Obstetric; letter; measurement; Pregnancy; priority journal; sampling; Time Factors

The effect of hydroxyapatite thickness on metal ion release from stainless steel substrates - Sousa, S.R.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
The corrosion behaviour of 350 stainless steel coated with hydroxyapatite, HA, by plasma spraying was studied in Hank's Balanced Salt Solution, HBSS, and compared with that of polished passivated surfaces. Two different nominal thicknesses, 50 μm and 200 μm, corresponding to what one might consider a thin and a thick coating, respectively, were used. Only HA coatings with a thickness of 200 μm were capable of reducing the electrical charge consumed at constant potential to values lower than those measured for polished surfaces. However, no HA detachment occurred for both thicknesses, as opposed to what has been found in a previous work with Ti6A14V alloy coated with 50 μm HA. No iron, chromium or nickel were detected in solution by Atomic Absorption Spectroscopy with electrothermal atomization (ET-AAS). These elements were also absent from the bulk of the HA coating, both after a 6 month immersion period and electrochemical accelerated tests. The data indicate that in spite of the relatively low corrosion resistance of stainless steel as compared to that of titanium alloys, a thin (50 μm) HA coating prevents the release of metal ions, while remaining adherent to the substrate.The corrosion behaviour of 350 stainless steel coated with hydroxyapatite, HA, by plasma spraying was studied in Hank's Balanced Salt Solution, HBSS, and compared with that of polished passivated surfaces. Two different nominal thicknesses, 50 μm and 200 μm, corresponding to what one might consider a thin and a thick coating, respectively, were used. Only HA coatings with a thickness of 200 μm were capable of reducing the electrical charge consumed at constant potential to values lower than those measured for polished surfaces. However, no HA detachment occurred for both thicknesses, as opposed to what has been found in a previous work [1] with Ti6Al4V alloy coated with 50 μm HA. No iron, chromium or nickel were detected in solution by Atomic Absorption Spectroscopy with electrothermal atomization (ET-AAS). These elements were also absent from the bulk of the HA coating, both after a 6 month immersion period and electrochemical accelerated tests. The data indicate that in spite of the relatively low corrosion resistance of stainless steel as compared to that of titanium alloys, a thin (50 μm) HA coating prevents the release of metal ions, while remaining adherent to the substrate.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00134324Language of Original Document: EnglishCorrespondence Address: Sousa, S.R.; INEB, Instituto Engenharia Biomedica, Praca do Coronel Pacheco, 1, 4050 Porto, Portugal
Keywords: Absorption spectroscopy; atomic absorption spectrometry; Atomic absorption spectroscopy; Atomic spectroscopy; balanced salt solution; Calcium Compounds; Chromium; comparative study; conference paper; Corrosion; Corrosion behaviour; Electric charge; electrochemistry; Hank balanced salt solution; hydroxyapatite; immersion; Inorganic coatings; Ions; Iron; metal ion; Metal ion release; Nickel; Plasma spraying; priority journal; Stainless steel; Stainless steel substrates; Substrates; thickness; Thickness effect; Titanium; Titanium alloys

Electrochemical and surface modifications on N +-ion implanted Ti-6A1-4V immersed in HBSS - Leitão, E.; Sa, C.; Silva, R.A.; Barbosa, M.A.; Ali, H. (Corrosion ScienceCorros. Sci., 1995)
The effect of nitrogen-ion implantation on the electrochemical behaviour of Ti-6Al-4V in a simulated physiological solution (HBSS-Hank's balanced salt solution) was studied by open-circuit potential versus time and cyclic polarization techniques, with the aim of characterizing better the surface prior to biological testing and to choose the most appropriate nitrogen-ion fluence. Three fluences (10 15, 10 16 and 10 17 ions/cm 2) were used. The 10 16 ions/cm 2 N + fluence produced the lowest corrosion rate under passive conditions. The highest fluence originated a large increase in the corrosion rate and inhibited the formation of a calcium- and phosphate-rich layer on the electrode surface. © 1995.
Cited By (since 1996): 37Export Date: 21 November 2012Source: ScopusCODEN: CRRSALanguage of Original Document: EnglishCorrespondence Address: Leitão, E.; INEB-Instituto de Engenharia Biomédica, Praca do Coronel Pacheco, 1, 4050 Porto, Portugal
Keywords: Biological testing; Characterization; Corrosion; Corrosion rate; Cyclic polarization technique; Electrochemical behaviour; electrochemistry; Hank balanced salt solution; Ion implantation; materials testing; Nitrogen ion implanted titanium aluminum vanadium alloy; Nitrogen-ion fluence; Open circuit potential; Passivation; Polarization; Simulated physiological solution; Solutions; Surface modification; Surface treatment; Titanium alloys

Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions: Structure and properties of the composites - Santos, J.D.; Reis, R.L.; Monteiro, F.J.; Knowles, J.C.; Hastings, G.W. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
Phosphate- and silicate-based glasses were added to hydroxyapatite in order to improve its mechanical properties and to fabricate composites with different degrees of bioactivity. A strong chemical bonding was obtained between hydroxyapatite and the phosphate-based glasses leading to samples approaching theoretical density, according to density measurements and scanning electron microscopy. Bioglass® additions led to the formation of a complex calcium phosphate silicate which hampered the reinforcement process. The fracture toughness of the hydroxyapatite-glass composites was shown to be within the 1.1-1.2 MPam(1/2) range, which is double that determined for sintered hydroxyapatite. A 2 μm thick apatite layer was observed on the surface of the hydroxyapatite-glass composites after 48 h immersion in a simulated human blood plasma, whereas only a few apatite crystals were detected on sintered hydroxyapatite after 7 days immersion. From the results obtained we anticipate that the composites might show a higher rate of bone bonding, leading to enhanced bioactivity.Phosphate- and silicate-based glasses were added to hydroxyapatite in order to improve its mechanical properties and to fabricate composites with different degrees of bioactivity. A strong chemical bonding was obtained between hydroxyapatite and the phosphate-based glasses leading to samples approaching theoretical density, according to density measurements and scanning electron microscopy. Bioglass (R) additions led to the formation of a complex calcium phosphate silicate which hampered the reinforcement process. The fracture toughness of the hydroxyapatite-glass composites was shown to be within the 1.1-1.2 MPa m 1/2 range, which is double that determined for sintered hydroxyapatite. A 2 μm thick apatite layer was observed on the surface of the hydroxyapatite-glass composites after 48 h immersion in a simulated human blood plasma, whereas only a few apatite crystals were detected on sintered hydroxyapatite after 7 days immersion. From the results obtained we anticipate that the composites might show a higher rate of bone bonding, leading to enhanced bioactivity.
Cited By (since 1996): 41Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00120303Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB-National Inst. Biomedical Engn., Department Metallurgical Engineering, FEUP, University of Porto, Rua dos Bragas 4099-Porto Codex, Portugal
Keywords: Adhesion; article; Bioactivity; Bioglass; Biomaterials; Bone; bone prosthesis; calcium phosphate; chemical binding; Chemical bonds; chemical composition; Chemical structure; Complex calcium phosphate silicate; Composite materials; crystal; density; Density measurement (specific gravity); glass; Human blood plasma; hydroxyapatite; Liquid phase sintering; Mechanical properties; Mechanics; phosphate; Phosphates; plasma; priority journal; Scanning electron microscopy; silicate; Silicates; Sintering; Structure (composition); surface property; thickness

Plasma surface treatment and PACVD on Ti alloys for surgical implants - Rie, K.-T.; Stucky, T.; Silva, R.A.; Leitao, E.; Bordji, K.; Jouzeau, J.-Y.; Mainard, D. (Surface and Coatings TechnologySurf. Coat. Technol., 1995)
To improve the poor surface hardness and wear resistance of titanium alloys used for surgical implants undergoing wear TiA16V4 and TiA15Fe2.5 have been plasma nitrided. TiN and other sublayers are formed by plasma nitriding. To increase the thickness of the outermost TiN layer the samples have been coated with TiN by PACVD following plasma nitriding. The produced layers have been characterized in terms of microstructure, layer composition, hardness depth profiles. The evaluation of corrosion resistance and biocompatibility revealed that the good properties of the untreated alloys have been well preserved. © 1995 Elsevier Science S.A.
Cited By (since 1996): 49Export Date: 21 November 2012Source: Scopusdoi: 10.1016/0257-8972(95)08316-2Language of Original Document: EnglishCorrespondence Address: Rie, K.-T.; Institut für Oberflächentechnik und plasmatechnische Werkstoffentwicklung, Technische Universität Braunschweig, Bienroder Weg 53, D-38108 Braunschweig, Germany
Keywords: Biocompatibility; Biomaterials; Characterization; Chemical vapor deposition; Corrosion resistance; hardness; Implants (surgical); Microstructure; Nitriding; PACVD; Plasma applications; Plasma assisted chemical vapor deposition; Plasma nitriding; Plasma surface treatment; Surface hardness; Surface treatment; Surfaces; Ti alloys; Titanium alloys; Wear resistance

Stainless steel corrosion products cause alterations on mouse spleen cellular populations - Tracana, R.B.; Pereira, M.L.; Abreu, A.M.; Sousa, J.P.; Carvalho, G.S. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
Stainless steel is a metallic biomaterial commonly used in orthopaedic surgery. In this study we looked at the effects of stainless steel corrosion products on spleen, in order to evaluate their potential immunotoxicological effects. For this purpose stainless steel, type AISI 316L, was electrochemically dissolved in a physiological salt solution. The final solution, containing 490 μg/ml Fe, 224 μg/ml Cr and 150 μg/ml Ni, was injected subcutaneously in mice. After several periods of time (4, 10 and 14 days) spleens were removed and analysed for: (a) their contents in Fe, Cr and Ni, (b) histological alterations, (c) enumeration of cellular populations. Results showed that stainless steel corrosion products accumulated in spleen, caused histological alterations, and induced changes in cellular populations. When compared to chromium and nickel, iron was the metal ion preferentially accumulated in spleen. The increase of the multinucleated giant cell population was accompanied by depletion of lymphocyte populations. This study indicates that stainless steel corrosion products can spread systemically and accumulate in spleen inducing histological and cellular alterations which may give rise to immunotoxicological consequences.Stainless steel is a metallic biomaterial commonly used in orthopaedic surgery. In this study we looked at the effects of stainless steel corrosion products on spleen, in order to evaluate their potential immunotoxicological effects. For this purpose stainless steel, type AISI 316L, was electrochemically dissolved in a physiological salt solution. The final solution, containing 490 μg/ml Fe, 224 μg/ml Cr and 150 μg/ml Ni, was injected subcutaneously in mice. After several periods of time (4, 10 and 14 days) spleens were removed and analysed for: (a) their contents in Fe, Cr and Ni, (b) histological alterations, (c) enumeration of cellular populations. Results showed that stainless steel corrosion products accumulated in spleen, caused histological alterations, and induced changes in cellular populations. When compared to chromium and nickel, iron was the metal ion preferentially accumulated in spleen. The increase of the multinucleated giant cell population was accompanied by depletion of lymphocyte populations. This study indicates that stainless steel corrosion products can spread systematically and accumulate in spleen inducing histological and cellular alterations which may give rise to immunotoxicological consequences.
Cited By (since 1996): 19Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00121249Language of Original Document: EnglishCorrespondence Address: Tracana, R.B.; Natl. Inst. Biomedical Engineering, INEB, Praca Coronel Pacheco 1, 4000 Porto, Portugal
Keywords: animal cell; animal experiment; animal tissue; Animalia; article; Biocompatibility; biomaterial; cell population; Cells; Chromium; Chronoamperometry; controlled study; Corrosion; Corrosion products; Dissolution; electrochemistry; giant cell; histology; immunology; immunotoxicity; Immunotoxicological effects; Ions; Iron; Lymphocyte; lymphocyte subpopulation; male; mouse; Nickel; nonhuman; orthopedic surgery; priority journal; sodium chloride; Spleen; spleen cell; Stainless steel; Steel corrosion; subcutaneous drug administration; toxicity

Surface modifications of glass-reinforced hydroxyapatite composites - Santos, J.D.; Jha, L.J.; Monteiro, F.J. (BiomaterialsBIOMATERIALS, 1995)
Surface modifications of glass-reinforced hydroxyapatite composites immersed in a simulated physiological solution were studied using X-ray photoelectron spectroscopy, scanning electron microscopy and energy dispersive X-ray spectroscopy. In the first stages of the apatite formation process, calcium and silicon ions were leached out from the surface of the composites. After 12 days of immersion, apatite crystals were detected on the surface indicating bioactive behaviour. Sodium ions attributed to sodium sulphate were also found in the apatite layer. Bound water on the surface also increased with immersion time.Surface modifications of glass-reinforced hydroxyapatite composites immersed in a simulated physiological solution were studied using X-ray photoelectron spectroscopy, scanning electron microscopy and energy dispersive X-ray spectroscopy. In the first stages of the apatite formation process, calcium and silicon ions were leached out from the surface of the composites. After 12 days of immersion, apatite crystals were detected on the surface indicating bioactive behaviour. Sodium ions attributed to sodium sulphate were also found in the apatite layer. Bound water on the surface also increased with immersion time.
Cited By (since 1996): 24Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/0142-9612(95)91124-HPubMed ID: 7492715Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Dept Metallurgical Engineering, FEUP, University of Porto, Rua dos Bragas 4099-Porto Codex, PortugalChemicals/CAS: Biocompatible Materials; Calcium, 7440-70-2; Glass; Hydroxyapatites; Phosphorus, 7723-14-0; Silicon, 7440-21-3; Sodium, 7440-23-5
Keywords: Apatite; article; Bioactive glass; Biocompatible Materials; Biomaterials; Calcium; chemical composition; Composite materials; Electron Probe Microanalysis; glass; Glass reinforced hydroxyapatite composites; Hydrogen-Ion Concentration; hydroxyapatite; Hydroxyapatites; immersion; Ions; Leaching; Microscopy, Electron, Scanning; Phosphates; phosphorus; priority journal; Scanning electron microscopy; Silicon; Sodium; sodium chloride; sodium sulfate; Spectrometry, X-Ray Emission; Spectroscopy; Surface modification; Surface Properties; surface property; Surface treatment; Water; X ray; X ray photoelectron spectroscopy; X ray spectroscopy

Mouse inflammatory response to stainless steel corrosion products - Tracana, R.B.; Sousa, J.P.; Carvalho, G.S. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1994)
Corrosion occurs regularly following long-term implantation of stainless steel. Little is known about the inflammatory and immunological potential of stainless steel corrosion products. AISI 316L stainless steel was anodically dissolved in a physiologically solution, HBSS, through a chronoamperometric process by imposing an external constant current of 0.5 mA. The solution, containing 245 μg of Fe, 112 μg of Cr, 75 μg of Ni and 13 μg of Mo, was injected in the peritoneal cavity of male C57BL/6 mice. Five animals were used per survival period of time: 4, 16, 24, and 48 h, 1, 2, 4, 8 and 16 weeks. Three control mice per survival period of time were injected with HBSS. For each assay, peritoneal samples were analysed not only for the total number of cells but also for the percentages of macrophages, lymphocytes and polymorphonuclear (PMN) cells, which were estimated by differential counting on Wright-stained cytocentrifuge preparations. Our follow-up study showed that stainless steel corrosion products induced an acute inflammatory response for a period of one week as demonstrated by the influx of PMN cells and macrophages. In contrast neither a chronic inflammation nor an immune response was observed indicating that the stainless steel solution caused a minor tissue response.A follow-up study of the changes to mouse peritoneal cell populations, succeeding intraperitoneal injection of stainless steel corrosion products, in order to assess the inflammatory response to such metals was presented. AISI stainless steel was anodically dissolved in a physiologically solution, Hank's balanced salt solution (HBSS), which was injected in the peritoneal cavity of male mice. Five animals were designated per survival time interval of 4, 16, 24, and 48 h, 1, 2, 4, 8 and 16 weeks. Three control mice per survival period of time were treated with HBSS. For each assay, peritoneal samples were tested for total number of cells and percentages of macrophages, lymphocytes and polymorphonuclear (PMN) cells. The follow-up study revealed that stainless steel corrosion products induced an acute inflammatory response for a duration of one week as shown by the influx of PMN cells and macrophages. In contrast, neither a chronic inflammation nor an immune response was noted suggesting that stainless steel solution caused a minor tissue response.
Cited By (since 1996): 15Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00120337Language of Original Document: EnglishCorrespondence Address: Tracana, R.B.; Nat. Inst. Biomedical Engineering, Praca Coronel Pacheco 14000 Porto, Portugal
Keywords: animal cell; animal experiment; Animalia; article; Assays; Cell Count; Cells; Chromium; Chronoamperometry; controlled study; Corrosion; Dissolution; follow up; immune response; immunology; Inflammation; Inflammatory response; Iron; Lymphocyte; Lymphocytes; macrophage; Macrophages; male; metal implantation; Mice (animal); molybdenum; mouse; Nickel; nonhuman; Peritoneal cavity; Polymorphonuclear; polymorphonuclear cell; priority journal; Stainless steel; time; Tissue; Wright stained cytocentrifuge